Are coffee silverskin extracts safe for topical use? An in vitro and in vivo approach - Rodrigues, F.; Pereira, C.; Pimentel, F. B.; Alves, R. C.; Ferreira, M.; Sarmento, B.; Helena Amaral, M.; Oliveira, M. Beatriz P. P. (Industrial Crops and Products, 2015)

Coffee silverskin: A possible valuable cosmetic ingredient - Rodrigues, Francisca; Palmeira-de-Oliveira, Ana; das Neves, Jose; Sarmento, Bruno; Helena Amaral, M.; Oliveira, M. Beatriz P. P. (Pharmaceutical Biology, 2015)

Combined C4d and CD3 immunostaining predicts immunoglobulin (Ig)A nephropathy progression - Faria, B.; Henriques, C.; Matos, A. C.; Daha, M. R.; Pestana, M.; Seelen, M. (Clinical and Experimental Immunology, 2015)

Cortical and trabecular bone in pediatric end-stage kidney disease - Carvalho, Catarina G.; Pereira, Renata C.; Gales, Barbara; Salusky, Isidro B.; Wesseling-Perry, Katherine (Pediatric Nephrology, 2015)

Finite element analysis of pectus carinatum surgical correction via a minimally invasive approach - Neves, Sara C.; Pinho, A. C. M.; Fonseca, Jaime C.; Rodrigues, Nuno F.; Henriques-Coelho, Tiago; Correia-Pinto, Jorge; Vilaca, Joao L. (Computer Methods in Biomechanics and Biomedical Engineering, 2015)

The interactions between municipal socioeconomic status and age on hip fracture risk - Oliveira, C.M.; Economou, T.; Bailey, T.; Mendona, D.; Pina, M.F. (Osteoporosis International, 2015)

Modulation of the inflammatory response to chitosan through M2 macrophage polarization using pro-resolution mediators - Vasconcelos, Daniela P.; Costa, Madalena; Amaral, Isabel F.; Barbosa, Mario A.; Aguas, Artur P.; Barbosa, Judite N. (Biomaterials, 2015)

Optic disc segmentation using the sliding band filter - Dashtbozorg, Behdad; Mendonca, Ana Maria; Campilho, Aurelio (Computers in Biology and Medicine, 2015)

Rehab@home: a tool for home-based motor function rehabilitation - Faria, Carlos; Silva, Jorge; Campilho, Aurelio (Disability and rehabilitation. Assistive technology, 2015)

The role of the surface on microglia function: implications for central nervous system tissue engineering - Pires, Liliana R.; Rocha, Daniela N.; Ambrosio, Luigi; Pego, Ana Paula (Journal of the Royal Society, Interface / the Royal Society, 2015)

Safety and toxicity concerns of orally delivered nanoparticles as drug carriers - Araujo, Francisca; Shrestha, Neha; Granja, Pedro L.; Hirvonen, Jouni; Santos, Helder A.; Sarmento, Bruno (Expert opinion on drug metabolism & toxicology, 2015)

Study of paraffin-embedded colon cancer tissue using terahertz spectroscopy - Wahaia, Faustino; Kasalynas, Irmantas; Seliuta, Dalius; Molis, Gediminas; Urbanowicz, Andrzej; Carvalho Silva, Catia D.; Carneiro, Fatima; Valusis, Gintaras; Granja, Pedro L. (Journal of Molecular Structure, 2015)

Terahertz spectroscopy for the study of paraffin-embedded gastric cancer samples - Wahaia, Faustino; Kasalynas, Irmantas; Seliuta, Dalius; Molis, Gediminas; Urbanowicz, Andrzej; Silva, Catia D. Carvalho; Carneiro, Fatima; Valusis, Gintaras; Granja, Pedro L. (Journal of Molecular Structure, 2015)

Actively targeted cetuximab conjugated γ-poly(glutamic acid)-docetaxel nanomedicines for epidermal growth factor receptor over expressing colon cancer cells - Maya, S.; Sarmento, B.; Lakshmanan, V.-K.; Menon, D.; Jayakumar, R. (Journal of Biomedical Nanotechnology, 2014)
Receptor targeted therapy is advantageous in overcoming the toxicity burden of conventional cancer chemotherapeutics. Over expression of epidermal growth factor receptor (EGFR) on cancer cells and its role in metastasis, malignancy and drug resistance in many human cancers lead to its selection as a promising target for cancer treatment. The present work investigated the preparation and characterization of docetaxel (DTXL) loaded γ-poly (glutamic acid) (γ-PGA) nanoparticles (Nps) conjugated with EGFR antibody (Cetuximab, CET) targeted to colon cancer cells (HT-29), highly over expressing EGFR. The flow cytometric analysis revealed two fold increased cellular uptake of CET-DTXL-γ-PGA Nps by HT-29 (EGFR +ve) cells compared to that of IEC-6 (EGFR-ve) cells confirming the active targeting. Cytotoxicity assays (MTT and LDH) showed superior anti-proliferative activity of CET-DTXL-γ-PGA NPs over DTXL-γ-PGA Nps against HT-29 cells. The cell cycle analysis indicated that CET-DTXL-γ-PGA NPs induced cell death in enhanced percentage of HT-29 cells by undergoing cell cycle arrest in G2/M phase compared to that of DTXL-γ-PGA Nps. The mechanism of cancer cell death was analyzed via apoptotic and mitochondrial membrane potential assays and showed that targeted Nps treatment reduced the mitochondrial membrane potential thereby inducing enhanced HT-29 cell death (apoptosis and necrosis). The biodistribution of targeted and non-targeted Nps were analyzed in vivo in Swiss albino mice using NIR imaging. ICG-CET-DTXL-γ-PGA Nps (targeted) and ICG-DTXL-γ-PGA Nps (non-targeted) followed the similar biodistribution pattern in vivo, but with different elimination time. In short, CET-DTXL-γ-PGA nanoparticles enhance the tumor selective therapeutic efficacy for colon cancer. Copyright © 2014 American Scientific Publishers All rights reserved.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Cetuximab; colon cancer; Docetaxel; Epidermal growth factor receptor; Poly(γ-glutamic acid) nanoparticles; Targeted nanomedicines

Adsorbed fibrinogen enhances production of bone- and angiogenic-related factors by monocytes/macrophages - Maciel, J.; Oliveira, M.I.; Colton, E.; McNally, A.K.; Oliveira, C.; Anderson, J.M.; Barbosa, M.A. (Tissue Engineering - Part A, 2014)
Macrophages are phagocytic cells with great importance in guiding multiple stages of inflammation and tissue repair. By producing a large number of biologically active molecules, they can affect the behavior of other cells and events, such as the foreign body response and angiogenesis. Since protein adsorption to biomaterials is crucial for the inflammatory process, we addressed the ability of the pro-inflammatory molecule fibrinogen (Fg) to modulate macrophage behavior toward tissue repair/regeneration. For this purpose, we used chitosan (Ch) as a substrate for Fg adsorption. Freshly isolated human monocytes were seeded on Ch substrates alone or previously adsorbed with Fg, and allowed to differentiate into macrophages for 10 days. Cell adhesion and morphology, formation of foreign body giant cells (FBGC), and secretion of a total of 80 cytokines and growth factors were evaluated. Both substrates showed similar numbers of adherent macrophages along differentiation as compared with RGD-coated surfaces, which were used as positive controls. Fg did not potentiate FBGC formation. In addition, actin cytoskeleton staining revealed the presence of punctuate F-actin with more elongated and interconnecting cells on Ch substrates. Antibody array screening and quantification of inflammation- and wound-healing-related factors indicated an overall reduction in Ch-based substrates versus RGD-coated surfaces. At late times, most inflammatory agents were down-regulated in the presence of Fg, in contrast to growth factor production, which was stimulated by Fg. Importantly, on Ch+Fg substrates, fully differentiated macrophages produced significant amounts of macrophage inflammatory protein-1delta (MIP-1δ), platelet-derived growth factor-BB, bone morphogenetic protein (BMP)-5, and BMP-7 compared with Ch alone. In addition, other important factors involved in bone homeostasis and wound healing, such as growth hormone, transforming growth factor-β3, and insulin-like growth factor-binding proteins, as well as several angiogenic mediators, including endocrine gland-derived vascular endothelial factor, fibroblast growth factor-7, and placental growth factor, were significantly promoted by Fg. This work provides a new perspective on the inflammatory response in the context of bone repair/regeneration mediated by a pro-inflammatory protein (Fg) adsorbed onto a biomaterial (Ch) that does not otherwise exhibit osteogenic properties. © Copyright 2014, Mary Ann Liebert, Inc.
Cited By (since 1996):1Export Date: 21 November 2014

Age-period-cohort effects in the incidence of hip fractures: Political and economic events are coincident with changes in risk - Alves, S.M.; Castiglione, D.; Oliveira, C.M.; de Sousa, B.; Pina, M.F. (Osteoporosis International, 2014)
Summary: An age-period cohort model was fitted to analyse time effects on hip fracture incidence rates by sex (Portugal, 2000-2008). Rates increased exponentially with age (age effect). Incidence rates decreased after 2004 for women and were random for men (period effect). New but comprehensive fluctuations in risk were coincident with major political/economic changes (cohort effect). Introduction: Healthcare improvements have allowed prevention but have also increased life expectancy, resulting in more people being at risk. Our aim was to analyse the separate effects of age, period and cohort on incidence rates by sex in Portugal, 2000-2008. Methods: From the National Hospital Discharge Register, we selected admissions (aged ≥49 years) with hip fractures (ICD9-CM, codes 820.x) caused by low/moderate trauma (falls from standing height or less), readmissions and bone cancer cases. We calculated person-years at risk using population data from Statistics Portugal. To identify period and cohort effects for all ages, we used an age-period-cohort model (1-year intervals) followed by generalised additive models with a negative binomial distribution of the observed incidence rates of hip fractures. Results: There were 77,083 hospital admissions (77.4% women). Incidence rates increased exponentially with age for both sexes (age effect). Incidence rates fell after 2004 for women and were random for men (period effect). There was a general cohort effect similar in both sexes; risk of hip fracture altered from an increasing trend for those born before 1930 to a decreasing trend following that year. Risk alterations (not statistically significant) coincident with major political and economic change in the history of Portugal were observed around birth cohorts 1920 (stable-increasing), 1940 (decreasing-increasing) and 1950 (increasing-decreasing only among women). Conclusions: Hip fracture risk was higher for those born during major economically/politically unstable periods. Although bone quality reflects lifetime exposure, conditions at birthmay determine future risk for hip fractures. © International Osteoporosis Foundation and National Osteoporosis Foundation 2013.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Age-period-cohort; Hip fractures; Osteoporosis; Population-based study; Time trend

Antihyperglycemic Potential of Incretins Orally Delivered via Nano and Microsystems and Subsequent Glucoregulatory Effects - Araujo, Francisca; Shrestha, Neha; Granja, Pedro L.; Hirvonen, Jouni; Santos, Helder A.; Sarmento, Bruno (Current Pharmaceutical Biotechnology, 2014)

Atomic force microscopy measurements reveal multiple bonds between Helicobacter pylori blood group antigen binding adhesin and Lewis b ligand - Parreira, P.; Shi, Q.; Magalhaes, A.; Reis, C.A.; Bugaytsova, J.; Boren, T.; Leckband, D.; Martins, M.C.L. (Journal of the Royal Society, Interface / the Royal Society, 2014)

An Automatic Graph-Based Approach for Artery/Vein Classification in Retinal Images - Dashtbozorg, Behdad; Mendonca, Ana Maria; Campilho, Aurelio (Ieee Transactions on Image Processing, 2014)

Bioactivity of surface tethered Osteogenic Growth Peptide motifs - Panseri, Silvia; Russo, Laura; Montesi, Monica; Taraballi, Francesca; Cunha, Carla; Marcacci, Maurilio; Cipolla, Laura (Medchemcomm, 2014)

A biocomposite of collagen nanofibers and nanohydroxyapatite for bone regeneration - Ribeiro, Nilza; Sousa, Susana R.; van Blitterswijk, Clemens A.; Moroni, Lorenzo; Monteiro, Fernando J. (Biofabrication, 2014)

Biodistribution and pharmacokinetics of Dapivirine-loaded nanoparticles after vaginal delivery in mice - Das Neves, J.; Araújo, F.; Andrade, F.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Pharmaceutical Research, 2014)
Purpose: To assess the potential of polymeric nanoparticles (NPs) to affect the genital distribution and local and systemic pharmacokinetics (PK) of the anti-HIV microbicide drug candidate dapivirine after vaginal delivery. Methods: Dapivirine-loaded, poly(ethylene oxide)-coated poly(epsilon-caprolactone) (PEO-PCL) NPs were prepared by a nanoprecipitation method. Genital distribution of NPs and their ability to modify the PK of dapivirine up to 24 h was assessed after vaginal instillation in a female mouse model. Also, the safety of NPs upon daily administration for 14 days was assessed by histological analysis and chemokine/cytokine content in vaginal lavages. Results: PEO-PCL NPs (180-200 nm) were rapidly eliminated after administration but able to distribute throughout the vagina and lower uterus, and capable of tackling mucus and penetrate the epithelial lining. Nanocarriers modified the PK of dapivirine, with higher drug levels being recovered from vaginal lavages and vaginal/lower uterine tissues as compared to a drug suspension. Systemic drug exposure was reduced when NPs were used. Also, NPs were shown safe upon administration for 14 days. Conclusions: Dapivirine-loaded PEO-PCL NPs were able to provide likely favorable genital drug levels, thus attesting the potential value of using this vaginal drug delivery nanosystem in the context of HIV prophylaxis. © 2014 Springer Science+Business Media New York.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: HIV/AIDS; microbicides; poly(ε-caprolactone); pre-exposure prophylaxis; vaginal drug delivery

Building and repairing the heart: What can we learn from embryonic development? - Freire, AG; Resende, TP; Pinto-Do-Ó, P. (BioMed Research International, 2014)
Mammalian heart formation is a complex morphogenetic event that depends on the correct temporal and spatial contribution of distinct cell sources. During cardiac formation, cellular specification, differentiation, and rearrangement are tightly regulated by an intricate signaling network. Over the last years, many aspects of this network have been uncovered not only due to advances in cardiac development comprehension but also due to the use of embryonic stem cells (ESCs) in vitro model system. Additionally, several of these pathways have been shown to be functional or reactivated in the setting of cardiac disease. Knowledge withdrawn from studying heart development, ESCs differentiation, and cardiac pathophysiology may be helpful to envisage new strategies for improved cardiac repair/regeneration. In this review, we provide a comparative synopsis of the major signaling pathways required for cardiac lineage commitment in the embryo and murine ESCs. The involvement and possible reactivation of these pathways following heart injury and their role in tissue recovery will also be discussed. © 2014 Ana G. Freire et al.

Can artificial neural networks be used to predict the origin of ozone episodes? - Fontes, T.; Silva, L.M.; Silva, M. P.; Barros, N.; Carvalho, A. C. (Science of the Total Environment, 2014)
Tropospheric ozone is a secondary pollutant having a negative impact on health and environment. To control and minimize such impact the European Community established regulations to promote a clean air all over Europe. However, when an episode is related with natural mechanisms as Stratosphere-Troposphere Exchanges (STE), the benefits of an action plan to minimize precursor emissions are inefficient. Therefore, this work aims to develop a tool to identify the sources of ozone episodes in order to minimize misclassification and thus avoid the implementation of inappropriate air quality plans. For this purpose, an artificial neural network model - the Multilayer Perceptron - is used as a binary classifier of the source of an ozone episode. Long data series, between 2001 and 2010, considering the ozone precursors, 7Be activity and meteorological conditions were used. With this model, 2-7% of a mean error was achieved, which is considered as a good generalization. Accuracy measures for imbalanced data are also discussed. The MCC values show a good performance of the model (0.65-0.92). Precision and F1-measure indicate that the model specifies a little better the rare class. Thus, the results demonstrate that such a tool can be used to help authorities in the management of ozone, namely when its thresholds are exceeded due natural causes, as the above mentioned STE. Therefore, the resources used to implement an action plan to minimize ozone precursors could be better managed avoiding the implementation of inappropriate measures. © 2014 Elsevier B.V.
Keywords: artificial neural network; Classification; Human health; Ozone; Stratosphere; Troposphere

Cellular strategies to promote vascularisation in tissue engineering applications - Costa-Almeida, R.; Granja, P.L.; Soares, R.; Guerreiro, S.G. (European Cells and Materials, 2014)
Vascularisation is considered to be one of the greatest challenges in tissue engineering. Different strategies exist but cell-based approaches have emerged as a promising therapy to achieve successful vascularisation. The use of endothelial cells to engineer vascularised tissues has been extensively investigated. This field of research has evolved with the discovery of endothelial progenitor cells, a subpopulation with a high regenerative potential. However, the survival of endothelial cell populations alone seems to be impaired. To overcome this problem, co-culture systems, involving supporting cells, like mural cells, fibroblasts, or more tissue-specific cells have been developed. Endothelial cells benefit from the extracellular matrix components and growth factors produced by the supporting cells, which results in neovessel stabilisation and maturation. The use of endothelial progenitor cells in co-culture systems appears to be a promising strategy to promote vascularisation in approaches of increasing complexity. Herein, the authors provide an overview of the cellular strategies that can be used for increasing vascularisation in tissue engineering and regeneration.
Keywords: angiogenesis; Cellular therapies; Co-culture models; Endothelial progenitor cells; Regeneration

Characterization of hLF1-11 immobilization onto chitosan ultrathin films, and its effects on antimicrobial activity - Costa, F.; Maia, S.; Gomes, J.; Gomes, P.; Martins, M.C.L. (Acta Biomaterialia, 2014)
hLF1-11 (GRRRRSVQWCA) is an antimicrobial peptide (AMP) with high activity against methicillin-resistant Staphylococcus aureus (MRSA), the most prevalent species in implant-associated infection. In this work, the effect of the surface immobilization on hLF1-11 antimicrobial activity was studied. Immobilization was performed onto chitosan thin films as a model for an implant coating due to its reported osteogenic and antibacterial properties. Chitosan thin films were produced by spin-coating on gold surfaces. hLF1-11 was immobilized onto these films by its C-terminal cysteine in an orientation that exposes the antimicrobial activity-related arginine-rich portion of the peptide. Two levels of exposure (with and without a polyethylene glycol (PEG) spacer) were analyzed. Covalent immobilization was further compared with the AMP physical adsorption onto chitosan films. Surfaces were characterized using ellipsometry, contact angle measurements, atomic force microscopy, infrared and X-ray photoelectron spectroscopies and using a fluorimetric assay for hLF1-11 quantification. Surface antimicrobial activity was assessed through surface adhesion and viability assays using an MRSA (S. aureus ATCC 33591). The incorporation of hLF1-11 increased significantly bacterial adhesion to chitosan films. However, the presence of hLF1-11, namely when immobilized through a PEG spacer, decreased the viability of adherent bacteria with regard to the control surface. These results demonstrated that hLF1-11 after covalent immobilization by its cysteine can maintain activity, particularly if a spacer is applied. However, further studies, exploring the opposite orientation or the same C-terminal orientation, but non-cysteine related, can help to clarify the potential of the hLF1-11 immobilization strategy. © 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Antimicrobial peptides (AMP); Bacterial adhesion; chitosan; Surface characterization; Surface immobilization

Chitosan cross-linked docetaxel loaded EGF receptor targeted nanoparticles for lung cancer cells - Maya, S.; Sarmento, B.; Lakshmanan, V.-K.; Menon, D.; Seabra, V.; Jayakumar, R. (International Journal of Biological Macromolecules, 2014)
Lung cancer, associated with the up-regulated epidermal growth factor receptor (EGFR) led to the development of EGFR targeted anticancer therapeutics. The biopolymeric nanoparticles form an outstanding system for the targeted delivery of therapeutic agents. The present work evaluated the in vitro effects of chitosan cross-linked γ-poly(glutamic acid) (γ-PGA) nanoparticles (Nps) loaded with docetaxel (DTXL) and decorated with Cetuximab (CET), targeted to EGFR over-expressing non-small-cell-lung-cancer (NSCLC) cells (A549). CET-DTXL-γ-PGA Nps was prepared by ionic gelation and CET conjugation via EDC/NHS chemistry. EGFR specificity of targeted Nps was confirmed by the higher uptake rates of EGFR +ve A549 cells compared to that of EGFR -ve cells (NIH3T3). The cytotoxicity of Nps quantified using cell based (MTT/LDH) and flowcytometry (Cell-cycle analysis, Annexin V/PI and JC-1) assays showed superior antiproliferative activity of CET-DTXL-γ-PGA Nps over DTXL-γ-PGA Nps. The A549 cells treated with CET-DTXL-γ-PGA NPs underwent a G2/M phase cell cycle arrest followed by reduction in mitochondrial membrane potential of A549 cells, inducing apoptosis and necrosis resulting in enhanced cancer cell death. CET-DTXL-γ-PGA Nps exhibited enhanced cellular internalization and therapeutic activity, by actively targeting EGFR on NSCLC cells and hence could be an effective alternative to non-specific, conventional chemotherapy by increasing its efficiency by many folds. © 2014 Elsevier B.V.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Cetuximab; chitosan; Epidermal growth factor receptor; Poly(γ-glutamic acid) nanoparticles; Targeted nanoparticles

Chitosan-modified porous silicon microparticles for enhanced permeability of insulin across intestinal cell monolayers - Shrestha, N.; Shahbazi, M.-A.; Araújo, F.; Zhang, H.; Mäkilä, E.M.; Kauppila, J.; Sarmento, B.; Salonen, J.J.; Hirvonen, J.T.; Santos, H.A. (Biomaterials, 2014)
Porous silicon (PSi) based particulate systems are emerging as an important drug delivery system due to its advantageous properties such as biocompatibility, biodegradability and ability to tailor the particles' physicochemical properties. Here, annealed thermally hydrocarbonized PSi (AnnTHCPSi) and undecylenic acid modified AnnTHCPSi (AnnUnTHCPSi) microparticles were developed as a PSi-based platform for oral delivery of insulin. Chitosan (CS) was used to modify the AnnUnTHCPSi microparticles to enhance the intestinal permeation of insulin. Surface modification with CS led to significant increase in the interaction of PSi microparticles with Caco-2/HT-29 cell co-culture monolayers. Compared to pure insulin, the CS-conjugated microparticles significantly improved the permeation of insulin across the Caco-2/HT-29 cell monolayers, with ca. 20-fold increase in the amount of insulin permeated and ca. 7-fold increase in the apparent permeability (Papp) value. Moreover, among all the investigated particles, the CS-conjugated microparticles also showed the highest amount of insulin associated with the mucus layer and the intestinal Caco-2 cells and mucus secreting HT-29 cells. Our results demonstrate that CS-conjugated AnnUnTHCPSi microparticles can efficiently enhance the insulin absorption across intestinal cells, and thus, they are promising microsystems for the oral delivery of proteins and peptides across the intestinal cell membrane. © 2014 Elsevier Ltd.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Cell monolayers; chitosan; Diabetes; Insulin; Microparticles; Porous silicon

Co-association of methotrexate and SPIONs into anti-CD64 antibody-conjugated PLGA nanoparticles for theranostic application - Moura, Catarina Costa; Segundo, Marcela A.; das Neves, Jose; Reis, Salette; Sarmento, Bruno (International Journal of Nanomedicine, 2014)

Collagen surface modified poly(ε-caprolactone) scaffolds with improved hydrophilicity and cell adhesion properties - Sousa, I.; Mendes, A.; Pereira, R.F.; Bártolo, P.J. (Materials Letters, 2014)
Poly(ε-caprolactone) (PCL)/collagen scaffolds were produced using a four-step procedure comprising (i) the fabrication of PCL scaffolds through an additive bioextrusion system, (ii) the PCL surface modification using a plasma treatment, (iii) the acrylic acid (AAc) grafting by ultraviolet (UV) polymerization, and (iv) the immobilization of collagen into the scaffold surface through the carbodiimide chemistry. This procedure allowed the quick fabrication of highly porous scaffolds with interconnected pores, well-defined internal architecture and improved cell adhesion properties. The immobilization of collagen into the PCL surface led to a significant enhancement in the hydrophilicity, while the biological tests showed a further improvement in the adhesion of fibroblast cells. These results indicate that the collagen surface modification is an effective strategy to render the hydrophobic nature of PCL and overcome the limited cell interaction of 3D PCL scaffolds. © 2014 Elsevier B.V.
Keywords: BioExtruder; Collagen; poly(ε-caprolactone); Scaffold; Surface modification

Complexity-loss in fetal heart rate dynamics during labor as a potential biomarker of acidemia - Costa, Madalena D.; Schnettler, William T.; Amorim-Costa, Celia; Bernardes, Joao; Costa, Antonia; Goldberger, Ary L.; Ayres-de-Campos, Diogo (Early Human Development, 2014)

A critical appraisal of the evidence for using cardiotocography plus ECG ST interval analysis for fetal surveillance in labor. Part I: the randomized controlled trials - Olofsson, Per; Ayres-de-Campos, Diogo; Kessler, Joerg; Tendal, Britta; Yli, Branka M.; Devoe, Lawrence (Acta Obstetricia Et Gynecologica Scandinavica, 2014)
Si

Crucial CD8+ T-lymphocyte cytotoxic role in amphotericin B nanospheres efficacy against experimental visceral leishmaniasis - Costa Lima, S.A.; Silvestre, R.; Barros, D.; Cunha, J.; Baltazar, M.T.; Dinis-Oliveira, R.J.; Cordeiro-da-Silva, A. (Nanomedicine: Nanotechnology, Biology, and Medicine, 2014)
This work aims to develop poly(d,l-lactide-co-glycolide) (PLGA)-nanospheres containing amphotericin B (AmB) with suitable physicochemical properties and anti-parasitic activity for visceral leishmaniasis (VL) therapy. When compared with unloaded-PLGA-nanospheres, the AmB-loaded PLGA-nanospheres displayed an increased particle size without affecting the polydispersity and its negative surface charge. AmB stability in the PLGA-nanospheres was >90% over 60-days at 30°C. The AmB-PLGA-nanospheres demonstrated significant in vitro and in vivo efficacy and preferential accumulation in the visceral organs. In addition, an immune-modulatory effect was observed in mice treated with AmB-PLGA-nanospheres, correlating with improved treatment efficacy. The in vitro cytotoxic response of the T-lymphocytes revealed that AmB-PLGA-nanospheres efficacy against VL infection was strictly due to the action of CD8+- but not CD4+-T lymphocytes. Overall, we demonstrate a crucial role for CD8+ cytotoxic T lymphocytes in the efficacy of AmB-PLGA nanospheres, which could represent a potent and affordable alternative for VL therapy. From the Clinical Editor: This study demonstrates a crucial role for CD8+ T lymphocytes in eliminating visceral leishmaniasis in a murine model by enhancing the cytotoxic efficacy of CD8+ T-cells via amphotericin-B-PLGA nanospheres, paving a way to a unique, potentially more potent and cost-effective therapeutic strategy. © 2014 Elsevier Inc.
Keywords: Amphotericin B; Immune-modulation; Poly(d,l-lactide-co-glycolide) nanospheres; Visceral leishmaniasis

Development and evaluation of an algorithm for computer analysis of maternal heart rate during labor - Pinto, P.; Bernardes, J.; Costa-Santos, C.; Amorim-Costa, C.; Silva, M.; Ayres-de-Campos, D. (Computers in Biology and Medicine, 2014)
Background: Maternal heart rate (MHR) recordings are morphologically similar and sometimes coincident with fetal heart rate (FHR) recordings and may be useful for maternal-fetal monitoring if appropriately interpreted. However, similarly to FHR, visual interpretation of MHR features may be poorly reproducible. Methods: A computer algorithm for on-line MHR analysis was developed based on a previously existing version for FHR analysis. Inter-observer and computer-observer agreement and reliability were assessed in 40 one-hour recordings obtained from 20 women during the last 2. h of labor. Agreement and reliability were evaluated for the detection of basal MHR, long-term variability (LTV), accelerations and decelerations, using proportions of agreement (PA) and Kappa statistic (K), with 95% confidence intervals (95% CI). Changes in MHR characteristics between the first and the second hour of the tracings were also evaluated. Results: There was a statistically significant inter-observer and computer-observer agreement and reliability in estimation of basal MHR, accelerations, decelerations and LTV, with PA values ranging from 0.72 (95% CI: 0.62-0.79) to 1.00 (95% CI: 0.99-1.00), and K values ranging from 0.44 (95% CI: 0.28-0.60) to 0.89 (95% CI: 0.82-0.96). Moreover, basal MHR, number of accelerations and LTV were significantly higher in the last hour of labor, when compared to the initial hour. Discussion: The developed algorithm for on-line computer analysis of MHR recordings provided good to excellent computer-observer agreement and reliability. Moreover, it allowed an objective detection of MHR changes associated with labor progression, providing more information about the interpretation of maternal-fetal monitoring during labor. © 2014 Elsevier Ltd.
Keywords: Agreement; Cardiotocography; computer analysis; Fetal heart rate; Maternal heart rate; reliability

Differences between external and internal fetal heart rate monitoring during the second stage of labor: a prospective observational study - Nunes, Ines; Ayres-de-Campos, Diogo; Costa-Santos, Cristina; Bernardes, Joao (Journal of Perinatal Medicine, 2014)

Dissecting the signaling pathways associated with the oncogenic activity of MLK3 P252H mutation - Velho, Sergia; Pinto, Ana; Licastro, Danilo; Oliveira, Maria Jose; Sousa, Filipa; Stupka, Elia; Seruca, Raquel (Bmc Cancer, 2014)

DNAJB4 molecular chaperone distinguishes WT from mutant E-cadherin, determining their fate in vitro and in vivo - Simões-Correia, J.; Silva, D.I.; Melo, S.; Figueiredo, J.; Caldeira, J.; Pinto, M.T.; Girão, H.; Pereira, P.; Seruca, R. (Human Molecular Genetics, 2014)
E-cadherin (Ecad) is a well-known invasion suppressor and its loss of expression is common in invasive carcinomas. Germline Ecad mutations are the only known genetic cause of hereditary diffuse gastric cancer (HDGC), demonstrating the causative role of Ecad impairment in gastric cancer. HDGC-associated Ecad missense mutations can lead to folding defects and premature proteasome-dependent endoplasmic reticulum-associated degradation (ERAD), but the molecular determinants for this fate were unidentified. Using a Drosophilabased genetic screen, we found that Drosophila DnaJ-1 interacts with wild type (WT) and mutant human Ecad in vivo. DnaJ (Hsp40) homolog, subfamily B, member 4 (DNAJB4), the human homolog of DnaJ-1, influences Ecad localization and stability even in the absence of Ecad endogenous promoter, suggesting a post-transcriptional level of regulation. Increased expression of DNAJB4 leads to stabilization of WT Ecad in the plasma membrane, while it induces premature degradation of unfolded HDGC mutants in the proteasome. The interaction between DNAJB4 and Ecad is direct, and is increased in the context of the unfolded mutant E757K, especially when proteasome degradation is inhibited, suggesting that DNAJB4 is a molecular mediator of ERAD. Post-translational regulation of native Ecad by DNAJB4 molecular chaperone is sufficient to influence cell adhesion in vitro. Using a chick embryo chorioallantoic membrane assay with gastric cancer derived cells, we demonstrate that DNAJB4 stimulates the anti-invasive function of WT Ecad in vivo. Additionally, the expression of DNAJB4 and Ecad is concomitantly decreased in human gastric carcinomas. Altogether, we demonstrate that DNAJB4 is a sensor of Ecad structural features that might contribute to gastric cancer progression. © The Author 2013. Published by Oxford University Press. All rights reserved.

Dysregulation of T cell receptor N-glycosylation: A molecular mechanism involved in ulcerative colitis - Dias, A.M.; Dourado, J.; Lago, P.; Cabral, J.; Marcos-Pinto, R.; Salgueiro, P.; Almeida, C.R.; Carvalho, S.; Fonseca, S.; Lima, M.; Vilanova, M.; Dinis-Ribeiro, M.; et al. (Human Molecular Genetics, 2014)
The incidence of inflammatory bowel disease is increasing worldwide and the underlying molecular mechanisms are far from being fully elucidated. Herein, we evaluated the role of N-glycosylation dysregulation in T cells as a key mechanism in the ulcerative colitis (UC) pathogenesis. The evaluation of the branched N-glycosylation levelsandprofile of intestinalTcell receptor (TCR)wereassessedin colonic biopsies fromUCpatientsand healthy controls. Expression alterations of the glycosyltransferase gene MGAT5 were also evaluated. We demonstrated thatUCpatients exhibit a dysregulation ofTCRbranchedN-glycosylationonlamina propriaTlymphocytes. Patients with severe UC showed the most pronounced defect on N-glycan branching in T cells. Moreover, UC patients showed a significant reduction of MGAT5 gene transcription in T lymphocytes. In this study, we disclose for the first time that a deficiency in branched N-glycosylation on TCR due to a reduced MGAT5 gene expression is a new molecular mechanism underlying UC pathogenesis, being a potential novel biomarker with promising clinical and therapeutic applications. © The Author 2013. Published by Oxford University Press. All rights reserved.

Effect of cell density on mesenchymal stem cells aggregation in RGD-alginate 3D matrices under osteoinductive conditions - Maia, F.R.; Lourenço, A.H.; Granja, P.L.; Gonçalves, R.M.; Barrias, C.C. (Macromolecular Bioscience, 2014)
Cellular activities in 3D are differentially affected by several matrix-intrinsic and extrinsic factors. This study highlights the relevance of optimizing initial cell densities when establishing 3D cultures for specific applications. Independently of the entrapping density, MSCs cultured within RGD-alginate hydrogels showed steady-state levels of metabolic activity and were in a nearly non-proliferative state, but recovered "normal" activity levels when retrieved from 3D matrices and re-cultured as monolayers. Importantly, high-densities promoted the establishment of cell-cell contacts with formation of multicellular clusters stabilized by endogenous ECM, and also stimulated MSCs osteogenic differentiation. These MSC-ECM microtissues may be used as building blocks for tissue engineering. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: alginate hydrogels; encapsulation; Self-assembly; Tissue engineering

The effect of hyaluronan-based delivery of stromal cell-derived factor-1 on the recruitment of MSCs in degenerating intervertebral discs - Pereira, C.L.; Gonçalves, R.M.; Peroglio, M.; Pattappa, G.; D'Este, M.; Eglin, D.; Barbosa, M.A.; Alini, M.; Grad, S. (Biomaterials, 2014)
Intervertebral disc (IVD) degeneration is the leading cause of low back pain and disability in the active population. Transplantation of mesenchymal stem cells (MSCs) in a hydrogel carrier can induce regenerative effects in degenerated IVDs. Moreover, it was found that degenerative discs release chemoattractants effective in MSC recruitment. Based on these findings, we hypothesized that an injectable hydrogel that can enhance the number of migrated MSCs in the IVD and provide a suitable matrix for their survival and differentiation would be ideal. The purpose of this study was to evaluate the potential of a thermoreversible hyaluronan-poly(N-isopropylacrylamide) (HAP) hydrogel as chemoattractant delivery system to recruit human MSCs in degenerative IVDs. The results demonstrate that HAP hydrogels containing stromal cell derived factor-1 (SDF-1) significantly increased the number of MSCs migrating into nucleotomized discs compared with discs treated with only HAP or SDF-1 in solution. HAP hydrogels releasing SDF-1 enhanced both the number of recruited cells and their migration distance in the IVD tissue. Furthermore, this phenomenon was dependent on MSC donor age. In conclusion, HAP SDF-1 is effective for the recruitment of stem cells in the IVD, thus opening new possibilities for the development of regenerative therapies based on endogenous cell migration. © 2014 Elsevier Ltd.
Keywords: Intervertebral disc; Mesenchymal Stem Cells; Recruitment; Stromal cell derived factor-1; Thermoreversible hyaluronan hydrogel

Endoplasmic Reticulum Degradation-Enhancing alpha-Mannosidase-like Protein 1 Targets Misfolded HLA-B27 Dimers for Endoplasmic Reticulum-Associated Degradation - Guiliano, David B.; Fussell, Helen; Lenart, Izabela; Tsao, Edward; Nesbeth, Darren; Fletcher, Adam J.; Campbell, Elaine C.; Yousaf, Nasim; Williams, Sarah; Santos, Susana; Cameron, Amy; Towers, Greg J.; et al. (Arthritis & Rheumatology, 2014)

Engineering proteolytically-degradable artificial extracellular matrices - Fonseca, Keila B.; Granja, Pedro L.; Barrias, Cristina C. (Progress in Polymer Science, 2014)

Eradication of Helicobacter pylori: Past, present and future - Lopes, D.; Nunes, C.; Martins, M.C.L.; Sarmento, B.; Reis, S. (Journal of Controlled Release, 2014)
Helicobacter pylori is the major cause of chronic gastritis and peptic ulcers. Since the classification as a group 1 carcinogenic by International Agency for Research on Cancer, the importance of the complete H. pylori eradication has obtained a novel meaning. Hence, several studies have been made in order to deepen the knowledge in therapy strategies. However, the current therapy presents unsatisfactory eradication rates due to the lack of therapeutic compliance, antibiotic resistance, the degradation of antibiotics at gastric pH and their insufficient residence time in the stomach. Novel approaches have been made in order to overcome these limitations. The purpose of this review is to provide an overview about the current therapy and its limitations, while highlighting the possibility of using micro- and nanotechnology to develop gastric drug delivery systems, overcoming these difficulties in the future. © 2014 Elsevier B.V.
Keywords: Drug delivery; Helicobacter pylori; Microparticles; nanoparticles; Treatment

An evaluation of the latest in vitro tools for drug metabolism studies - Costa, A.; Sarmento, B.; Seabra, V. (Expert Opinion on Drug Metabolism and Toxicology, 2014)
Introduction: Drugs are indispensable for human welfare nevertheless there is a lack of safe drugs. Obtaining pharmacokinetics information, especially metabolism, is a requirement during preclinical and clinical drug development so that in vitro tools represent a simple path where it is possible to assess drug toxicity and predict drug safety in humans. Areas covered: This review covers the latest in vitro tools developed for assessing drug toxicity in different organs. A special focus is given to hepatic models, as it is the main organ responsible for drug metabolism and consequently bioactivation and detoxification reactions. Three-dimensional culture models have been widely developed, resembling in vivo-like conditions, and are also discussed in this review. Expert opinion: Several in vitro tools to assess hepatic drug metabolism have been developed, however, novel in vitro methods to investigate extra-hepatic drug metabolism still need to be improved. These methods are able to reduce the number of animal used in preclinical experiments, but in vivo tests are mandatory for drug approval and commercialization. © 2014 Informa UK, Ltd.
Keywords: Hepatic metabolism; in vitro models; Intestinal metabolism; Pulmonary metabolism; Renal metabolism

External uterine contractions signal analysis in relation to labor progression and dystocia - Gonçalves, H.; Pinto, P.; Ayres-de-Campos, D.; Bernardes, J. (IFMBE Proceedings, 2014)
Labor dystocia is a major cause of operative delivery, which is associated with increased risks for both mother and fetus. We assessed linear and non-linear dynamics of external uterine contraction signals, in relation to labor progression and dystocia. Linear time domain, spectral and entropy methods were used to analyze external uterine contraction recordings obtained during the last two hours of labor, in 28 cases with normal and 27 cases with operative deliveries (forceps, vacuum or caesarean). Progression of labor was associated with a statistically significant increase in most linear time domain and spectral indices, both in normal and operative deliveries, whereas most entropy indices increased in normal deliveries, but did not change in operative deliveries. On the other hand, when compared with normal births, operative deliveries were associated with significantly increased entropy indices before the last hour of labor and significantly decreased (a probably associated) sympatho-vagal balance in the last hour of labor. Linear and non-linear analysis of external uterine contraction recordings may provide useful physiopathological and clinical information on the progression of labor and the diagnosis of dystocia. © Springer International Publishing Switzerland 2014.
Keywords: Cardiotocography; Dystocia; entropy; External uterine contractions; Spectral analysis

Extracellular matrix stiffness and composition jointly regulate the induction of malignant phenotypes in mammary epithelium - Chaudhuri, Ovijit; Koshy, Sandeep T.; Branco da Cunha, Cristiana; Shin, Jae-Won; Verbeke, Catia S.; Allison, Kimberly H.; Mooney, David J. (Nature Materials, 2014)

Fetal behavioral dynamics in cephalic versus breech presentations - Gonçalves, H.; Ayres-de-Campos, D.; Bernardes, J. (Developmental Psychobiology, 2014)
Differences in fetal neurodevelopment can have important implications on future perceptual and learning capabilities. The aim of this study was to assess autonomic nervous system and complexity dynamics in fetal heart rate (FHR) tracings from 27 singleton fetuses in cephalic or breech presentations, matched for gestational age (37+3-40+4 weeks), weight, gender and outcome. Breeches exhibited significantly higher mean FHR and LF/(MF+HF) ratio, as well as lower entropy, denoting increased sympatho-vagal balance and decreased complexity, consistent with the occurrence of more active fetal behavioral states. These findings suggest that there are neurodevelopment differences between fetuses in cephalic and breech presentation.
Keywords: Breech presentation; Development; entropy; Fetal behavior; Heart rate; Spectral analysis

Fetal Behavioral Dynamics in Cephalic Versus Breech Presentations - Goncalves, Hernani; Ayres-de-Campos, Diogo; Bernardes, Joao (Developmental Psychobiology, 2014)

Fetal QRS detection and heart rate estimation: a wavelet-based approach - Almeida, Rute; Goncalves, Hernani; Bernardes, Joao; Rocha, Ana Paula (Physiological Measurement, 2014)

Field dimension and skill level constrain team tactical behaviours in small-sided and conditioned games in football - Silva, Pedro; Duarte, Ricardo; Sampaio, Jaime; Aguiar, Paulo; Davids, Keith; Araujo, Duarte; Garganta, Julio (Journal of Sports Sciences, 2014)
Si

Fluorescent bionanoprobes based on quantum dot-chitosan-O-phospho-L-serine conjugates for labeling human bone marrow stromal cells - Salgado, Christiane L.; Mansur, Alexandra A. P.; Mansur, Herman S.; Monteiro, Fernando J. M. (Rsc Advances, 2014)

Formulation and delivery of anti-HIV rectal microbicides: Advances and challenges - Nunes, Rute; Sarmento, Bruno; das Neves, Jose (Journal of Controlled Release, 2014)

Ganciclovir-resistant cytomegalovirus infection in renal transplantation - Vaz, R.; Barros, F.; Tavares, I.; Bustorff, M.; Ferreira, I.; Pestana, M. (Clinical Kidney Journal, 2014)
Keywords: cytomegalovirus infection; ganciclovir resistance

HA/TCP Scaffolds Obtained by Sucrose Crystal Leaching Method: Preliminary in vitro Evaluation - Rodrigues, Leonardo Ribeiro; Laranjeira, Marta de Sousa; Fernandes, Maria Helena; Monteiro, Fernando Jorge; de Carvalho Zavaglia, Cecilia Amelia (Materials Research-Ibero-American Journal of Materials, 2014)

Hippo pathway effectors control cardiac progenitor cell fate by acting as dynamic sensors of substrate mechanics and nanostructure - Mosqueira, D.; Pagliari, S.; Uto, K; Ebara, M; Romanazzo, S.; Escobedo-Lucea, C; Nakanishi, J; Taniguchi, A; Franzese, O; Di Nardo, P.; Goumans, MJ; Traversa, E; et al. (ACS Nano, 2014)
Stem cell responsiveness to extracellular matrix (ECM) composition and mechanical cues has been the subject of a number of investigations so far, yet the molecular mechanisms underlying stem cell mechano-biology still need full clarification. Here we demonstrate that the paralog proteins YAP and TAZ exert a crucial role in adult cardiac progenitor cell mechano-sensing and fate decision. Cardiac progenitors respond to dynamic modifications in substrate rigidity and nanopattern by promptly changing YAP/TAZ intracellular localization. We identify a novel activity of YAP and TAZ in the regulation of tubulogenesis in 3D environments and highlight a role for YAP/TAZ in cardiac progenitor proliferation and differentiation. Furthermore, we show that YAP/TAZ expression is triggered in the heart cells located at the infarct border zone. Our results suggest a fundamental role for the YAP/TAZ axis in the response of resident progenitor cells to the modifications in microenvironment nanostructure and mechanics, thereby contributing to the maintenance of myocardial homeostasis in the adult heart. These proteins are indicated as potential targets to control cardiac progenitor cell fate by materials design. © 2014 American Chemical Society.
Cited By (since 1996):4Export Date: 21 November 2014
Keywords: adult cardiac progenitor cell; cardiac differentiation; mechano- transduction; substrate nanotopography; YAP/TAZ

Human umbilical cord tissue-derived mesenchymal stromal cells attenuate remodeling after myocardial infarction by proangiogenic, antiapoptotic, and endogenous cell-activation mechanisms - Nascimento, D.S.; Mosqueira, D.; Sousa, L.M.; Teixeira, M.; Filipe, M.; Resende, TP; Araújo, A.F.; Valente, M.; Almeida, J.; Martins, J.P.; Santos, J.M.; Bárcia, R.N.; et al. (Stem Cell Research and Therapy, 2014)
Introduction. Among the plethora of cells under investigation to restore a functional myocardium, mesenchymal stromal cells (MSCs) have been granted considerable interest. However, whereas the beneficial effects of bone marrow MSCs (BM-MSCs) in the context of the diseased heart are widely reported, data are still scarce on MSCs from the umbilical cord matrix (UCM-MSCs). Herein we report on the effect of UCM-MSC transplantation to the infarcted murine heart, seconded by the dissection of the molecular mechanisms at play. Methods. Human umbilical cord tissue-derived MSCs (UCX®), obtained by using a proprietary technology developed by ECBio, were delivered via intramyocardial injection to C57BL/6 females subjected to permanent ligation of the left descending coronary artery. Moreover, medium produced by cultured UCX® preconditioned under normoxia (CM) or hypoxia (CMH) was collected for subsequent in vitro assays. Results: Evaluation of the effects upon intramyocardial transplantation shows that UCX® preserved cardiac function and attenuated cardiac remodeling subsequent to myocardial infarction (MI). UCX® further led to increased capillary density and decreased apoptosis in the injured tissue. In vitro, UCX®-conditioned medium displayed (a) proangiogenic activity by promoting the formation of capillary-like structures by human umbilical vein endothelial cells (HUVECs), and (b) antiapoptotic activity in HL-1 cardiomyocytes subjected to hypoxia. Moreover, in adult murine cardiac Sca- 1§ssup§+§esup§ progenitor cells (CPCs), conditioned medium enhanced mitogenic activity while activating a gene program characteristic of cardiomyogenic differentiation. Conclusions: UCX® preserve cardiac function after intramyocardial transplantation in a MI murine model. The cardioprotective effects of UCX® were attributed to paracrine mechanisms that appear to enhance angiogenesis, limit the extent of the apoptosis, augment proliferation, and activate a pool of resident CPCs. Overall, these results suggest that UCX® should be considered an alternative cell source when designing new therapeutic approaches to treat MI. © 2014 Nascimento et al.; licensee BioMed Central Ltd.
Cited By (since 1996):2Export Date: 21 November 2014

Hydrogel depots for local co-delivery of osteoinductive peptides and mesenchymal stem cells - Maia, F.R.; Barbosa, M.; Gomes, D.B.; Vale, N.; Gomes, P.; Granja, P.L.; Barrias, C.C. (Journal of Controlled Release, 2014)
The outcome of cell-based therapies can benefit from carefully designed cell carriers. A multifunctional injectable vehicle for the co-delivery of human mesenchymal stem cells (hMSCs) and osteoinductive peptides is proposed, to specifically direct hMSCs osteogenic differentiation. The osteogenic growth peptide (OGP) inspired the design of two peptides, where the bioactive portion of OGP was flanked by a protease-sensitive linker, or its scrambled sequence, to provide faster and slower release rates, respectively. Peptides were fully characterized and chemically grafted to alginate. Both OGP analogs released bioactive fragments in vitro, at different kinetics, which stimulated hMSCs proliferation and osteogenesis. hMSCs-laden OGP-alginate hydrogels were tested at an ectopic site in a xenograft mouse model. After 4 weeks, OGP-alginate hydrogels were more degraded and colonized by vascularized connective tissue than the control (without OGP). hMSCs were able to proliferate, migrate outward the hydrogels, produce endogenous extracellular matrix and mineralize it. Moreover, OGP-groups stimulated hMSCs osteogenesis, as compared with the control. Overall, the ability of the proposed platform to direct the fate of transplanted hMSCs in loco was demonstrated, and OGP-releasing hydrogels emerged as a potentially useful system to promote bone regeneration. © 2014 Elsevier B.V.
Keywords: Bone Regeneration; Co-delivery systems; Guided differentiation; Injectable alginate hydrogels; Mesenchymal Stem Cells; Osteoinductive peptides

Impact of 3-D printed PLA- and chitosan-based scaffolds on human monocyte/macrophage responses: Unraveling the effect of 3-D structures on inflammation - Almeida, C.R.; Serra, T.; Oliveira, M.I.; Planell, J.A.; Barbosa, M.A.; Navarro, M. (Acta Biomaterialia, 2014)
Recent studies have pointed towards a decisive role of inflammation in triggering tissue repair and regeneration, while at the same time it is accepted that an exacerbated inflammatory response may lead to rejection of an implant. Within this context, understanding and having the capacity to regulate the inflammatory response elicited by 3-D scaffolds aimed for tissue regeneration is crucial. This work reports on the analysis of the cytokine profile of human monocytes/macrophages in contact with biodegradable 3-D scaffolds with different surface properties, architecture and controlled pore geometry, fabricated by 3-D printing technology. Fabrication processes were optimized to create four different 3-D platforms based on polylactic acid (PLA), PLA/calcium phosphate glass or chitosan. Cytokine secretion and cell morphology of human peripheral blood monocytes allowed to differentiate on the different matrices were analyzed. While all scaffolds supported monocyte/macrophage adhesion and stimulated cytokine production, striking differences between PLA-based and chitosan scaffolds were found, with chitosan eliciting increased secretion of tumor necrosis factor (TNF)-α, while PLA-based scaffolds induced higher production of interleukin (IL)-6, IL-12/23 and IL-10. Even though the material itself induced the biggest differences, the scaffold geometry also impacted on TNF-α and IL-12/23 production, with chitosan scaffolds having larger pores and wider angles leading to a higher secretion of these pro-inflammatory cytokines. These findings strengthen the appropriateness of these 3-D platforms to study modulation of macrophage responses by specific parameters (chemistry, topography, scaffold architecture). © 2013 Acta Materialia Inc.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: 3-D scaffolds; Human macrophages; Inflammation; Rapid prototyping; Tissue engineering

The impact of nanoparticles on the mucosal translocation and transport of GLP-1 across the intestinal epithelium - Araújo, F.; Shrestha, N.; Shahbazi, M.-A.; Fonte, P.; Mäkilä, E.M.; Salonen, J.J.; Hirvonen, J.T.; Granja, P.L.; Santos, H.A.; Sarmento, B. (Biomaterials, 2014)
Glucagon like peptide-1 (GLP-1) is an incretin hormone that is in the pipeline for type 2 diabetes mellitus (T2DM) therapy. However, oral administration of GLP-1 is hindered by the harsh conditions of the gastrointestinal tract and poor bioavailability. In this study, three nanosystems composed by three different biomaterials (poly(lactide-co-glycolide) polymer (PLGA), Witepsol E85 lipid (solid lipid nanoparticles, SLN) and porous silicon (PSi) were developed and loaded with GLP-1 to study their permeability invitro. All the nanoparticles presented a size of approximately 200nm. The nanoparticles' interaction with the mucus and the intestinal cells were enhanced after coating with chitosan (CS). PSi nanosystems presented the best association efficiency (AE) and loading degree (LD), even though a high AE was also observed for PLGA nanoparticles and SLN. Among all the nanosystems, PLGA and PSi were the only nanoparticles able to sustain the release of GLP-1 in biological fluids when coated with CS. This characteristic was also maintained when the nanosystems were in contact with the intestinal Caco-2 and HT29-MTX cell monolayers. The CS-coated PSi nanoparticles showed the highest GLP-1 permeation across the intestinal invitro models. In conclusion, PLGA+CS and PSi+CS are promising nanocarriers for the oral delivery of GLP-1. © 2014 Elsevier Ltd.
Keywords: chitosan; Diabetes; Glucagon like peptide-1; nanoparticles; Oral delivery systems; Triple co-culture

Impact of the introduction of fetal central monitoring on hospital expenses with cardiotocographic paper - Amorim-Costa, C.; Ayres-de-Campos, D.; Costa-Santos, C.; Bernardes, J. (Journal of Obstetrics and Gynaecology, 2014)

In vitro analysis of the antibacterial effect of nanohydroxyapatite-ZnO composites - Grenho, L.; Jorge Monteiro, F.; Pia Ferraz, M. (Journal of Biomedical Materials Research - Part A, 2014)
Hydroxyapatite (HA) is a biocompatible and bioactive synthetic material for biomedical applications as it binds to bone and enhances bone tissue formation. Particularly, nanophased HA can mimic the dimensions of constituent components of natural tissues; can modulate enhanced osteoblast adhesion and resorption with long-term functionality of tissue engineered implants. However, HA does not inhibit bacteria from adhering onto its surface, and this has implications in the bone healing process required for patient recovery, since infection can lead to the implant failure. In the present work a composite that combines the favorable biological characteristics of nanohydroxyapatite (nanoHA) and, simultaneously, possesses antimicrobial activity as expressed by ZnO was synthesized. To determine whether the size of ZnO particles was playing an important role in inhibiting bacterial growth, ZnO particle of different sizes (from the microscale down to the nanoscale) and concentration were incorporated into nanoHA and tested. The composite samples were characterized by SEM, FT-IR, XRD, XPS and zeta potential. The antibacterial activity of the composites was investigated, as well as the biofilm formation, using both Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) microorganisms. The characterization revealed that ZnO particles were dispersed homogeneously within the nanoHA matrix. The composites antibacterial activity increased with decreasing ZnO particle size and increasing concentration. Biofilm formation tests revealed that the nanoHA-ZnO composites exhibit a strong effect against the common pathogens S. aureus and E. coli. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3726-3733, 2014. © 2013 Wiley Periodicals, Inc.
Keywords: Antibacterial; biofilm; Composite; Nanohydroxyapatite; zinc oxide

In vitro intestinal absorption of amino acid mixtures extracted from codfish (Gadus morhua L.) salting wastewater - Ferraro, V.; Ferreira Jorge, R.; Cruz, I.B.; Antunes, F.; Sarmento, B.; Castro, P.M.L.; Pintado, M.E. (International Journal of Food Science and Technology, 2014)
Summary: This study reports on the intestinal permeability of salt-containing mixtures of amino acids extracted from codfish salting wastewater. Permeability was evaluated in vitro using the Caco-2 cell line model; cell integrity during exposure to mixtures of amino acids was estimated by measuring the transepithelial electrical resistance (TEER). The effect of salt (NaCl) on the permeability and on the intestinal cell's integrity was also examined. Permeation rate (i.e. transport) was ≥95% for all amino acids except for creatine, for which it was 6%. Values for apparent permeability coefficients, Papp > 10-5 cm s-1, for mixture with isotonic concentration of NaCl suggest that amino acids are very likely to be absorbed in humans. Mixture with a hypertonic level of NaCl exerts a cytotoxic effect in intestinal cells resulting in a loss of epithelium integrity. Results show that isotonic mixture of amino acids extracted from codfish salting wastewater could be used in food, feed, cosmetic and pharmaceutical formulations. These applications could contribute to the fish industry sustainability. © 2013 Institute of Food Science and Technology.
Keywords: Absorption; Amino acids; Caco-2 cell; Codfish; Small intestine

Influence of nanohydroxyapatite surface properties on Staphylococcus epidermidis biofilm formation - Barros, J.; Grenho, L.; Manuel, C.M.; Ferreira, C.; Melo, L.; Nunes, O.C.; Monteiro, F.J.; Ferraz, M.P. (Journal of Biomaterials Applications, 2014)
Nanohydroxyapatite (nanoHA), due to its chemical properties, has appeared as an exceptionally promising bioceramic to be used as bone regeneration material. Staphylococcus epidermidis have emerged as major nosocomial pathogens associated with infections of implanted medical devices. In this work, the purpose was to study the influence of the nanoHA surface characteristics on S. epidermidis RP62A biofilm formation. Therefore, two different initial inoculum concentrations (Ci) were used in order to check if these would affect the biofilm formed on the nanoHA surfaces. Biofilm formation was followed by the enumeration of cultivable cells and by scanning electron microscopy. Surface topography, contact angle, total surface area and porosimetry of the biomaterials were studied and correlated with the biofilm data. The surface of nanoHA sintered at 830 (nanoHA830) showed to be more resistant to S. epidermidis attachment and accumulation than that of nanoHA sintered at 1000 (nanoHA1000). The biofilm formed on nanoHA830 presented differences in terms of structure, surface coverage and EPS production when compared to the one formed on nanoHA1000 surface. It was observed that topography and surface area of nanoHA surfaces had influence on the bacterial attachment and accumulation. Ci influenced bacteria attachment and accumulation on nanoHA surfaces over time. The choice of the initial inoculum concentration was relevant proving to have an effect on the extent of adherence thus being a critical point for human health if these materials are used in implantable devices. This study showed that the initial inoculum concentration and surface material properties determine the rate of microbial attachment to substrata and consequently are related to biofilm-associated infections in biomaterials. © The Author(s) 2013 Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: biofilm formation; biomaterial roughness; biomaterial surface area; Inoculum concentration; Nanohydroxyapatite

Influence of the stiffness of three-dimensional alginate/collagen-I interpenetrating networks on fibroblast biology - Branco da Cunha, C.; Klumpers, D.D.; Li, W.A.; Koshy, S.T.; Weaver, J.C.; Chaudhuri, O.; Granja, P.L.; Mooney, D.J. (Biomaterials, 2014)
Wound dressing biomaterials are increasingly being designed to incorporate bioactive molecules to promote healing, but the impact of matrix mechanical properties on the biology of resident cells orchestrating skin repair and regeneration remains to be fully understood. This study investigated whether tuning the stiffness of a model wound dressing biomaterial could control the behavior of dermal fibroblasts. Fully interpenetrating networks (IPNs) of collagen-I and alginate were fabricated to enable gel stiffness to be tuned independently of gel architecture, polymer concentration or adhesion ligand density. Three-dimensional cultures of dermal fibroblasts encapsulated within matrices of different stiffness were shown to promote dramatically different cell morphologies, and enhanced stiffness resulted in upregulation of key-mediators of inflammation such as IL-10 and COX-2. These findings suggest that simply modulating the matrix mechanical properties of a given wound dressing biomaterial deposited at the wound site could regulate the progression of wound healing. © 2014 Elsevier Ltd.
Keywords: ECM (extracellular matrix); Inflammation; Interpenetrating networks (IPNs); Mechanical properties; Wound dressing biomaterial; Wound healing

Injectable alginate hydrogels for cell delivery in tissue engineering - Bidarra, S.J.; Barrias, C.C.; Granja, P.L. (Acta Biomaterialia, 2014)
Alginate hydrogels are extremely versatile and adaptable biomaterials, with great potential for use in biomedical applications. Their extracellular matrix-like features have been key factors for their choice as vehicles for cell delivery strategies aimed at tissue regeneration. A variety of strategies to decorate them with biofunctional moieties and to modulate their biophysical properties have been developed recently, which further allow their tailoring to the desired application. Additionally, their potential use as injectable materials offers several advantages over preformed scaffold-based approaches, namely: Easy incorporation of therapeutic agents, such as cells, under mild conditions; minimally invasive local delivery; and high contourability, which is essential for filling in irregular defects. Alginate hydrogels have already been explored as cell delivery systems to enhance regeneration in different tissues and organs. Here, the in vitro and in vivo potential of injectable alginate hydrogels to deliver cells in a targeted fashion is reviewed. In each example, the selected crosslinking approach, the cell type, the target tissue and the main findings of the study are highlighted. © 2013 Acta Materialia Inc.
Keywords: Alginate; Cell delivery; Injectable; Regeneration; Tissue engineering

Injectable MMP-sensitive alginate hydrogels as hMSC delivery systems - Fonseca, K.B.; Gomes, D.B.; Lee, K.; Santos, S.G.; Sousa, A.; Silva, E.A.; Mooney, D.J.; Granja, P.L.; Barrias, C.C. (Biomacromolecules, 2014)
Hydrogels with the potential to provide minimally invasive cell delivery represent a powerful tool for tissue-regeneration therapies. In this context, entrapped cells should be able to escape the matrix becoming more available to actively participate in the healing process. Here, we analyzed the performance of proteolytically degradable alginate hydrogels as vehicles for human mesenchymal stem cells (hMSC) transplantation. Alginate was modified with the matrix metalloproteinase (MMP)-sensitive peptide Pro-Val-Gly-Leu-Iso-Gly (PVGLIG), which did not promote dendritic cell maturation in vitro, neither free nor conjugated to alginate chains, indicating low immunogenicity. hMSC were entrapped within MMP-sensitive and MMP-insensitive alginate hydrogels, both containing cell-adhesion RGD peptides. Softer (2 wt % alginate) and stiffer (4 wt % alginate) matrices were tested. When embedded in a Matrigel layer, hMSC-laden MMP-sensitive alginate hydrogels promoted more extensive outward cell migration and invasion into the tissue mimic. In vivo, after 4 weeks of subcutaneous implantation in a xenograft mouse model, hMSC-laden MMP-sensitive alginate hydrogels showed higher degradation and host tissue invasion than their MMP-insensitive equivalents. In both cases, softer matrices degraded faster than stiffer ones. The transplanted hMSC were able to produce their own collagenous extracellular matrix, and were located not only inside the hydrogels, but also outside, integrated in the host tissue. In summary, injectable MMP-sensitive alginate hydrogels can act as localized depots of cells and confer protection to transplanted cells while facilitating tissue regeneration. © 2013 American Chemical Society.
Cited By (since 1996):3Export Date: 21 November 2014

Injectable pectin hydrogels produced by internal gelation: PH dependence of gelling and rheological properties - Moreira, H.R.; Munarin, F.; Gentilini, R.; Visai, L.; Granja, P.L.; Tanzi, M.C.; Petrini, P. (Carbohydrate Polymers, 2014)
The production of injectable pectin hydrogels by internal gelation with calcium carbonate is proposed. The pH of pectin was increased with NaOH or NaHCO3 to reach physiological values. The determination of the equivalence point provided evidence that the pH can be more precisely modulated with NaHCO3 than with NaOH. Degradation and inability to gel was observed for pectin solutions with pH 5.35 or higher. Therefore, pectin solutions with pH values varying from 3.2 (native pH) to 3.8 were chosen to produce the gels. The increase of the pH for the crosslinked hydrogels, as well as the reduction of the gelling time and their thickening, was dependent upon the amount of calcium carbonate, as confirmed by rheology. Hydrogel extracts were not cytotoxic for L-929 fibroblasts. On the overall, the investigated formulations represent interesting injectable systems providing an adequate microenvironment for cell, drug or bioactive molecules delivery. © 2013 Elsevier Ltd.
Cited By (since 1996):5Export Date: 21 November 2014
Keywords: Biomaterials; Internal gelation; Natural polymers; pectin; Tissue engineering

Kinetochore motors drive congression of peripheral polar chromosomes by overcoming random arm-ejection forces - Barisic, Marin; Aguiar, Paulo; Geley, Stephan; Maiato, Helder (Nature Cell Biology, 2014)

Long-term effects of chronic cocaine exposure throughout adolescence on anxiety and stress responsivity in a Wistar rat model - Alves, C.J.; Magalhães, A.; Melo, P.; De Sousa, L.; Tavares, M.A.; Monteiro, P.R.R.; Summavielle, T. (Neuroscience, 2014)
Adolescents display increased vulnerability to engage in drug experimentation. This is often considered a risk factor for later drug abuse. In this scenario, the permanent effects of cocaine exposure during adolescence on anxiety levels and stress responsivity, which may result in behavioral phenotypes prone to addiction, are now starting to be unveiled. Thus, the purpose of the present study was to evaluate the long-lasting effects of chronic cocaine administration during adolescence, on anxiety-like behavior and on stress response. Adolescent male Wistar rats were daily administered 45-mg cocaine/kg of body weight in three equal intraperitoneal doses with 1-h interval, from postnatal day (PND) 35 to 50. The effects of cocaine administration on anxiety levels, assessed in the Elevated Plus Maze (EPM), and on social stress response, assessed in the resident-intruder paradigm (R/I), were evaluated 10. days after withdrawal, when rats were reaching the adulthood. The underlying dopaminergic activity, and the corticosterone and testosterone levels were determined. Our results showed that cocaine induced long-lasting alterations in the hypothalamus-pituitary-adrenals (HPA) axis function and in testosterone levels. Such alterations resulted in significant and enduring changes in behavioral responses to environmental challenges, such as the EPM and R/I, including the evaluation of potential threats that may lead to high-risk behavior and low-benefit choices. This was further supported by an altered dopaminergic function in the amygdala and hippocampus. The present findings provide new insights into how the use of cocaine during adolescent development may modulate emotional behavior later in life. Compromised ability to recognize and deal with potential threats is an important risk factor to perpetuate compulsive drug seeking and relapse susceptibility. © 2014 IBRO.
Keywords: Adolescence; anxiety; Cocaine; corticosterone; Dopaminergic system; Social stress

Macrophages stimulate gastric and colorectal cancer invasion through EGFR Y 1086, c-Src, Erk1/2 and Akt phosphorylation and smallGTPase activity - Cardoso, A.P.; Pinto, M.L.; Pinto, A.T.; Oliveira, M.I.; Pinto, M.T.; Gonçalves, R.; Relvas, J.B.; Figueiredo, C.; Seruca, R.; Mantovani, A.; Mareel, M.; Barbosa, M.A.; et al. (Oncogene, 2014)
The interactions between cancer cells and their microenvironment are crucial for malignant progression, as they modulate invasion-related activities. Tumor-associated macrophages are generally considered allies in the process of tumor progression in several types of cancer, although their role on gastric and colorectal carcinomas is still poorly understood. In this report, we studied the influence of primary human macrophages on gastric and colorectal cancer cells, considering invasion, motility/migration, proteolysis and activated intracellular signaling pathways. We demonstrated that macrophages stimulate cancer cell invasion, motility and migration, and that these effects depend on matrix metalloproteinase (MMP) activity and on the activation of epidermal growth factor receptor (EGFR) (at the residue Y 1086), PLC-γ (phospholipase C-gamma) and Gab1 (GRB2-associated binding protein-1), as evidenced by siRNA (small interference RNA) experiments. Epidermal growth factor (EGF)-immunodepletion impaired macrophage-mediated cancer cell invasion and motility, suggesting that EGF is the pro-invasive and pro-motile factor produced by macrophages. Macrophages also induced gastric and colorectal cancer cell phosphorylation of Akt, c-Src and ERK1/2, and led to an increase of RhoA and Cdc42 activity. Interestingly, whereas macrophage-mediated cancer cell c-Src and ERK1/2 phosphorylation occurred downstream EGFR activation, Akt phosphorylation seems to be a parallel event, taking place in an EGFR-independent manner. The involvement of EGF, EGFR-downstream signaling partners and MMPs in macrophage-mediated invasion provides novel insights into the molecular crosstalk established between cancer cells and macrophages, opening new perspectives for the design of new and more efficient therapeutic strategies to counteract cancer cell invasion. © 2014 Macmillan Publishers Limited.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: cancer cell invasion; colon cancer; Gastric cancer; invasion-related signaling pathways; Macrophages; tumor microenvironment

Mad2 checkpoint gene silencing using epidermal growth factor receptor-targeted chitosan nanoparticles in non-small cell lung cancer model - Nascimento, A.V.; Singh, A.; Bousbaa, H.; Ferreira, D.; Sarmento, B.; Amiji, M.M. (Molecular Pharmaceutics, 2014)
RNA interference has emerged as a powerful strategy in cancer therapy because it allows silencing of specific genes associated with tumor progression and resistance. Mad2 is an essential mitotic checkpoint component required for accurate chromosome segregation during mitosis, and its complete abolition leads to cell death. We have developed an epidermal growth factor receptor (EGFR)-targeted chitosan system for silencing the Mad2 gene as a strategy to efficiently induce cell death in EGFR overexpressing human A549 non-small cell lung cancer cells. Control and EGFR-targeted chitosan nanoparticles loaded with small interfering RNAs (siRNAs) against Mad2 were formulated and characterized for size, charge, morphology, and encapsulation efficiency. Qualitative and quantitative intracellular uptake studies by confocal imaging and flow cytometry, respectively, showed time-dependent enhanced and selective intracellular internalization of EGFR-targeted nanoparticles compared to nontargeted system. Targeted nanoparticles showed nearly complete depletion of Mad2 expression in A549 cells contrasting with the partial depletion in the nontargeted system. Accordingly, Mad2-silencing-induced apoptotic cell death was confirmed by cytotoxicity assay and flow cytometry. Our results demonstrate that EGFR-targeted chitosan loaded with Mad2 siRNAs is a potent delivery system for selective killing of cancer cells.
Keywords: chitosan nanoparticles; Epidermal growth factor receptor; Mad2 gene; non-small cell lung cancer; RNA interference; tumor targeting

Magnetic Bioinspired Hybrid Nanostructured Collagen-Hydroxyapatite Scaffolds Supporting Cell Proliferation and Tuning Regenerative Process - Tampieri, Anna; Iafisco, Michele; Sandri, Monica; Panseri, Silvia; Cunha, Carla; Sprio, Simone; Savini, Elisa; Uhlarz, Marc; Herrmannsdoerfer, Thomas (Acs Applied Materials & Interfaces, 2014)

Matrix-driven formation of mesenchymal stem cell-extracellular matrix microtissues on soft alginate hydrogels - Maia, F.R.; Fonseca, K.B.; Rodrigues, G.; Granja, P.L.; Barrias, C.C. (Acta Biomaterialia, 2014)
Mesenchymal stem cells (MSCs) can be made to rearrange into microtissues in response to specific matrix cues, a process that depends on a balance between cell-matrix and cell-cell interactions. The effect of such cues, and especially their interplay, is still not fully understood, particularly in three-dimensional (3-D) systems. Here, the behaviour of human MSCs cultured within hydrogel matrices with tailored stiffness and composition was evaluated. MSC aggregation occurred only in more compliant matrices (G′ ≤ 120 Pa), when compared to stiffer ones, both in the presence and in the absence of matrix-bound arginine-glycine-aspartic acid cell-adhesion ligands (RGD; 0, 100 and 200 μM). Fibronectin assembly stabilized cell-cell contacts within aggregates, even in non-adhesive matrices. However, MSCs were able to substantially contract the artificial matrix only when RGD was present. Moreover, compliant matrices facilitated cell proliferation and provided an environment conducive for MSC osteogenic differentiation, even without RGD. Cell interactions with the original matrix became less important as time progressed, while the de novo-produced extracellular matrix became a more critical determinant of cell fate. These data provide further insights into the mechanisms by which MSCs sense their microenvironment to organize into tissues, and provide new clues to the design of cell-instructive 3-D matrices. © 2014 Published by Elsevier Ltd. on behalf of Acta Materialia Inc.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: cell aggregation; Cell traction; Cell-matrix interactions; Hydrogels; Viscoelastic properties

Microfluidics co-culture systems for studying tooth innervation - Pagella, Pierfrancesco; Neto, Estrela; Jimenez-Rojo, Lucia; Lamghari, Meriem; Mitsiadis, Thimios A. (Frontiers in Physiology, 2014)

Modified-chitosan/siRNA nanoparticles downregulate cellular CDX2 expression and cross the gastric mucus barrier - Sadio, A.; Gustafsson, J.K.; Pereira, B.; Gomes, C.P.; Hansson, G.C.; David, L.; Pêgo, A.P.; Almeida, R. (PLoS ONE, 2014)
Development of effective non-viral vectors is of crucial importance in the implementation of RNA interference in clinical routine. The localized delivery of siRNAs to the gastrointestinal mucosa is highly desired but faces specific problems such as the stability in gastric acidity conditions and the presence of the mucus barrier. CDX2 is a transcription factor critical for intestinal differentiation being involved in the initiation and maintenance of gastrointestinal diseases. Specifically, it is the trigger of gastric intestinal metaplasia which is a precursor lesion of gastric cancer. Its expression is also altered in colorectal cancer, where it may constitute a lineage-survival oncogene. Our main objective was to develop a nanoparticle-delivery system of siRNA targeting CDX2 using modified chitosan as a vector. CDX2 expression was assessed in gastric carcinoma cell lines and nanoparticles behaviour in gastrointestinal mucus was tested in mouse explants. We show that imidazolemodified chitosan and trimethylchitosan/siRNA nanoparticles are able to downregulate CDX2 expression and overpass the gastric mucus layer but not colonic mucus. This system might constitute a potential therapeutic approach to treat CDX2-dependent gastric lesions. © 2014 Sadio et al.

Modulation of human dermal microvascular endothelial cell and human gingival fibroblast behavior by micropatterned silica coating surfaces for zirconia dental implant applications - Laranjeira, M.S.; Carvalho, Â.; Pelaez-Vargas, A.; Hansford, D.; Ferraz, M.P.; Coimbra, S.; Costa, E.; Santos-Silva, A.; Fernandes, M.H.; Monteiro, F.J. (Science and Technology of Advanced Materials, 2014)
Dental ceramic implants have shown superior esthetic behavior and the absence of induced allergic disorders when compared to titanium implants. Zirconia may become a potential candidate to be used as an alternative to titanium dental implants if surface modifications are introduced. In this work, bioactive micropatterned silica coatings were produced on zirconia substrates, using a combined methodology of sol-gel processing and soft lithography. The aim of the work was to compare the in vitro behavior of human gingival fibroblasts (HGFs) and human dermal microvascular endothelial cells (HDMECs) on three types of silica-coated zirconia surfaces: flat and micropatterned (with pillars and with parallel grooves). Our results showed that cells had a higher metabolic activity (HGF, HDMEC) and increased gene expression levels of fibroblast-specific protein-1 (FSP-1) and collagen type I (COL I) on surfaces with pillars. Nevertheless, parallel grooved surfaces were able to guide cell growth. Even capillary tube-like networks of HDMEC were oriented according to the surface geometry. Zirconia and silica with different topographies have shown to be blood compatible and silica coating reduced bacteria adhesion. All together, the results indicated that microstructured bioactive coating seems to be an efficient strategy to improve soft tissue integration on zirconia implants, protecting implants from peri-implant inflammation and improving long-term implant stabilization. This new approach of micropatterned silica coating on zirconia substrates can generate promising novel dental implants, with surfaces that provide physical cues to guide cells and enhance their behavior. © 2014 National Institute for Materials Science.
Keywords: bacteria adhesion; Biomaterials; hemolysis; human dermal microvascular endothelial cells (HDMECs); human gingival fibroblasts (HGFs); Micropatterning; Soft lithography

Mucoadhesive polymers in the design of nano-drug delivery systems for administration by non-parenteral routes: A review - Sosnik, Alejandro; das Neves, Jose; Sarmento, Bruno (Progress in Polymer Science, 2014)

A Multicompartment Holder for Spinner Flasks Improves Expansion and Osteogenic Differentiation of Mesenchymal Stem Cells in Three-Dimensional Scaffolds - Teixeira, Graciosa Q.; Barrias, Cristina C.; Lourenco, Ana H.; Goncalves, Raquel M. (Tissue Engineering Part C-Methods, 2014)

Nanoparticle-based drug delivery to improve the efficacy of antiretroviral therapy in the central nervous system - Gomes, M.J.; Das Neves, J.; Sarmento, B. (International Journal of Nanomedicine, 2014)
Antiretroviral drug therapy plays a cornerstone role in the treatment of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome patients. Despite obvious advances over the past 3 decades, new approaches toward improved management of infected individuals are still required. Drug distribution to the central nervous system (CNS) is required in order to limit and control viral infection, but the presence of natural barrier structures, in particular the blood-brain barrier, strongly limits the perfusion of anti-HIV compounds into this anatomical site. Nanotechnology-based approaches may help providing solutions for antiretro-viral drug delivery to the CNS by potentially prolonging systemic drug circulation, increasing the crossing and reducing the efflux of active compounds at the blood-brain barrier, and providing cell/tissue-targeting and intracellular drug delivery. After an initial overview on the basic features of HIV infection of the CNS and barriers to active compound delivery to this anatomical site, this review focuses on recent strategies based on antiretroviral drug-loaded solid nanoparticles and drug nanosuspensions for the potential management of HIV infection of the CNS. © 2014 Gomes et al.
Keywords: Blood-brain barrier; drug targeting; Efflux transporters; HIV/AIDS; Protease inhibitors

Natriuretic peptide system modulation in uninephrectomized rats - Santos-Araújo, C.; Roncon-Albuquerque Jr., R.; Moreira-Rodrigues, M.; Henriques-Coelho, T.; Quelhas-Santos, J.; Faria, B.; Sampaio-Maia, B.; Leite-Moreira, A.F.; Pestana, M. (Experimental and Clinical Cardiology, 2014)
BACKGROUND: Cardiac activation of the natriuretic peptide (NP) system plays a major role in the renal adaptations to volume, expansion (VE). However, its role after uninephrectomy (Unx) remains to be elucidated. In the present study, we evaluated cardiac hemodynamics, plasma NP-Type B (BNP) levels nd NP receptor A (NPR-A) and C (NPR-C) expression in the renal cortex (RC) and medulla (RM) of Sham and Unx rats. METHODS: Male Wistar-Han rats (n=42) were randomly assigned to Unx or Sham surgery. Non-invasive blood pressure (BP), invasive left ventricular (LV) hemodynamics and natriuretic response to VE were performed and plasma was collected for BNP determination, 2, 10 and 26 weeks after surgery. In addition, samples from RC and RM were obtained for NPR-A and -C quantification (RT-PCR and western-blot). RESULTS: In Unx, blood pressure elevation and reduced natriuretic response to VE were observed. Although plasma BNP levels increased overtime, no LV dysfunction or myocardial BNP gene activation was observed in Unx. NPR-A mRNA in RC and RM were significantly increased in Unx at 26 weeks. This was accompanied by decreased NPR-C mRNA in the RM in Unx at 10 and 26 weeks, with no differences detected in the RC. CONCLUSIONS: In our experimentalmodel of Unx, progressive BP elevation and reduced natriuretic response to VE were accompanied by modulation of NPR-A and -C expression, in both the RC and RM, in the absence of cardiac activation of the NP system. Our results suggest a local renal modulation of the NP system after Unx. © 2013 et al.; licensee Cardiology Academic Press.
Keywords: BNP; Hypertension; Natriuretic peptide receptor; Uninephrectomy

Neonatal human dermal fibroblasts immobilized in RGD-alginate induce angiogenesis - Guerreiro, S.G.; Oliveira, M.J.; Barbosa, M.A.; Soares, R.; Granja, P.L. (Cell Transplantation, 2014)
Promoting angiogenesis in a damaged tissue is a major challenge for tissue regeneration. Recent findings in tissue engineering suggest that fibroblasts (FBs) play an important role in orchestrating the angiogenic process. Fibroblasts maintain the structural integrity of connective tissue by continuously secreting growth factors and extracellular matrix precursors, which are essential for endothelial cell (EC) adhesion and spreading, thus playing a crucial role in angiogenesis. We hypothesized that FBs immobilized in alginate gels grafted with the RGD peptidic sequence could influence the recruitment of ECs to improve vascularization. In this work, the modulation of immobilized human FBs within the 3D synthetic extracellular matrix was assessed. Experiments using cocultures of ECs and FBs in indirect contact as well as angiogenic assays were performed to assess the influence of FBs immobilized in RGD-alginate in ECs' viability, stabilization, sprouting, and assembly into capillary-like structures. This study demonstrates the ability of FBs immobilized within RGD-alginate microspheres to modulate and support capillary-like structures' assembly. These findings indicate that the microenvironment created by these stromal cells in the scaffold modulates capillary morphogenesis, thus stimulating angiogenesis in situ and can potentially be used in regenerative medicine in clinical scenarios where vascularization is essential. © 2014 Cognizant Comm. Corp.
Keywords: Alginate; angiogenesis; Endothelial cells (ECs); Fibroblasts (FBs); RGD peptide: Injectable biomaterials

Optimization of the production of solid Witepsol nanoparticles loaded with rosmarinic acid - Campos, D.A.; Madureira, A.R.; Gomes, A.M.; Sarmento, B.; Pintado, M.M. (Colloids and Surfaces B: Biointerfaces, 2014)
During the last decade there has been a growing interest in the formulation of new food and nutraceutical products containing compounds with antioxidant activity. Unfortunately, due to their structure, certain compounds such as polyphenols, in particular rosmarinic acid (RA) are not stable and may interact easily with matrices in which they are incorporated. To overcome such limitations, the formulation of loaded polyphenols nanoparticles can offer an efficient solution to protect such compounds. Based on this rationale, the aim of this study was to prepare solid lipid nanoparticles (SLNs) loaded with RA using a hot melt ultrasonication method, where Witepsol H15 was used as lipid and Polysorbate 80 (Tween 80) as surfactant, following a 32 fractional factorial design, resulting in the use of 3 different percentages of surfactant (viz. 1, 2 and 3%, v/v) and lipid (0.5, 1.0 and 1.5%, w/v). The stability of the nanoparticles systems were tested during 28d in aqueous solution stored at refrigeration temperature (ca. 5°C), tracking the mean particle size of different formulations by photon correlation spectroscopy. To confirm RA entrapment, thermal analyses of the nanoparticles by DSC and FTIR were performed. The association efficiencies percentages (AE%) were determined using HPLC to quantitatively assess the RA in supernatants. Results showed that Witepsol H15 produced nanoparticles with initial mean diameters between 270 and 1000nm, yet over time, a slight increase occurred, but without occurrence of aggregation. The AE% showed a high percentage of encapsulation (ca. 99%), which reveals low polyphenol releases from SLNs throughout storage time. In general, results showed a successful production of SLNs with properties that can be used to food applications. © 2013 Elsevier B.V.
Keywords: Optimization; Rosmarinic acid; SLNs; Witepsol

A PEX7-Centered Perspective on the Peroxisomal Targeting Signal Type 2-Mediated Protein Import Pathway - Rodrigues, Tony A.; Alencastre, Ines S.; Francisco, Tania; Brites, Pedro; Fransen, Marc; Grou, Claudia P.; Azevedo, Jorge E. (Molecular and Cellular Biology, 2014)

Plasma and urine renalase levels and activity during the recovery of renal function in kidney transplant recipients - Quelhas-Santos, J.; Soares-Silva, I.; Fernandes-Cerqueira, C.; Simões-Silva, L.; Ferreira, I.; Carvalho, C.; Coentrão, L.; Vaz, R.; Sampaio-Maia, B.; Pestana, M. (Experimental Biology and Medicine, 2014)
Renalase is a recently described enzyme secreted by the kidney into both plasma and urine, where it was suggested to degrade catecholamines contributing to blood pressure control. While there is a controversy regarding the relationship between renal function and plasma renalase levels, there is virtually no data in humans on plasma renalase activity as well as on both urine renalase levels and activity. We prospectively examined the time course of plasma and urine renalase levels and activity in 26 end-stage renal disease (ESRD) patients receiving a cadaver kidney transplant (cadaver kidney recipients [CKR]) before surgery and during the recovery of renal function up to day 90 post transplant. The relationship with sympathetic and renal dopaminergic activities was also evaluated. The recovery of renal function in CKR closely predicted decreases in plasma renalase levels (r = 0.88; P < 0.0001), urine renalase levels (r = 0.75; P < 0.0001) and urine renalase activity (r = 0.56; P < 0.03), but did not predict changes in plasma renalase activity (r = -0.02; NS). Plasma norepinephrine levels positively correlated with plasma renalase levels (r = 0.64, P < 0.002) as well as with urine renalase levels and activity (r = 0.47 P < 0.02; r = 0.71, P < 0.0005, respectively) and negatively correlated with plasma renalase activity (r = -0.57, P < 0.002). By contrast, plasma epinephrine levels positively correlated with plasma renalase activity (r = 0.67, P < 0.0001) and negatively correlated with plasma renalase levels (r = -0.62, P < 0.003). A significant negative relationship was observed between urine dopamine output and urine renalase levels (r = -0.48; P < 0.03) but not with urine renalase activity (r = -0.33, NS). We conclude that plasma and urine renalase levels closely depend on renal function and sympathetic nervous system activity. It is suggested that epinephrine-mediated activation of circulating renalase may occur in renal transplant recipients with good recovery of renal function. The increase in plasma renalase activity observed in ESRD patients and renal transplant recipients can be explained on the basis of reduced inhibition of the circulating enzyme. © 2014 by the Society for Experimental Biology and Medicine.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: catecholamines; CKD; renal function; renal transplant; renalase

Plasma Renalase in Chronic Kidney Disease: Differences and Similarities between Humans and Rats - Quelhas-Santos, Janete; Pestana, Manuel (Current hypertension reviews, 2014)

Poly(trimethylene carbonate-co-ε-caprolactone) promotes axonal growth - Rocha, D.N.; Brites, P.; Fonseca, C.; Pêgo, A.P. (PLoS ONE, 2014)
Mammalian central nervous system (CNS) neurons do not regenerate after injury due to the inhibitory environment formed by the glial scar, largely constituted by myelin debris. The use of biomaterials to bridge the lesion area and the creation of an environment favoring axonal regeneration is an appealing approach, currently under investigation. This work aimed at assessing the suitability of three candidate polymers - poly(ε-caprolactone), poly(trimethylene carbonate-co-ε-caprolactone) (P(TMC-CL)) (11:89 mol%) and poly(trimethylene carbonate) - with the final goal of using these materials in the development of conduits to promote spinal cord regeneration. Poly(L-lysine) (PLL) coated polymeric films were tested for neuronal cell adhesion and neurite outgrowth. At similar PLL film area coverage conditions, neuronal polarization and axonal elongation was significantly higher on P(TMC-CL) films. Furthermore, cortical neurons cultured on P(TMC-CL) were able to extend neurites even when seeded onto myelin. This effect was found to be mediated by the glycogen synthase kinase 3β (GSK3β) signaling pathway with impact on the collapsin response mediator protein 4 (CRMP4), suggesting that besides surface topography, nanomechanical properties were implicated in this process. The obtained results indicate P(TMC-CL) as a promising material for CNS regenerative applications as it promotes axonal growth, overcoming myelin inhibition. © 2014 Rocha et al.

The potential utility of chitosan micro/nanoparticles in the treatment of gastric infection - Gonçalves, I.C.; Henriques, P.C.; Seabra, C.L.; Martins, M.C.L. (Expert Review of Anti-Infective Therapy, 2014)
Gastric infections are mainly caused by Helicobacter pylori (H. pylori), a bacterium that colonizes the gastric mucosa of over 50% of the world's population. Chronic H. pylori infection has been associated with gastric diseases such as chronic gastritis, peptic ulcer and gastric adenocarcinoma. Current eradication treatment relies on antibiotic-based therapies that are unsuccessful in approximately 20% of the patients. Chitosan, a natural and cationic polysaccharide has been investigated in the treatment of H. pylori infection. Due to its mucoadhesive properties, it has been used in the form of micro/nanoparticles, polyelectrolyte complexes or coatings as antibiotic encapsulation systems for gastric delivery, but alternative molecules may also be incorporated. It has been recently proposed that chitosan can also be used for H. pylori binding and scavenging from the host stomach due to its antimicrobial/binding properties. In this manuscript, a brief description of the use of chitosan in H. pylori treatment is reviewed. © Informa UK, Ltd.
Keywords: Biomaterials; chitosan; Crosslinking; Drug delivery; Gastric cancer; Helicobacter pylori; Microspheres; mucoadhesion; nanoparticles; Polyelectrolytes

The predominance of M2-polarized macrophages in the stroma of low-hypoxic bladder tumors is associated with BCG immunotherapy failure - Lima, L.; Oliveira, D.; Tavares, A.; Amaro, T.; Cruz, R.; Oliveira, M.J.; Ferreira, J.A.; Santos, L. (Urologic Oncology: Seminars and Original Investigations, 2014)
Objective: Bacillus Calmette-Guérin (BCG) immunotherapy is the gold standard treatment for superficial bladder tumors with intermediate/high risk of recurrence or progression. However, approximately 30% of patients fail to respond to the treatment. Effective BCG therapy needs precise activation of the type 1 helper cells immune pathway. Tumor-associated macrophages (TAMs) often assume an immunoregulatory M2 phenotype and may directly interfere with the BCG-induced antitumor immune response. Thus, we aim to clarify the influence of TAMs, in particular of the M2 phenotype in stroma and tumor areas, in BCG treatment outcome. Patients and methods: The study included 99 patients with bladder cancer treated with BCG. Tumors resected before treatment were evaluated using immunohistochemistry for CD68 and CD163 antigens, which identify a lineage macrophage marker and a M2-polarized specific cell surface receptor, respectively. CD68+ and CD163+ macrophages were evaluated within the stroma and tumor areas, and high density of infiltrating cells spots were selected for counting. Hypoxia, an event known to modulate macrophage phenotype, was also assessed through hypoxia induced factor (HIF)-1α expression. Results: Patients in whom BCG failed had high stroma-predominant CD163+ macrophage counts (high stroma but low tumor CD163+ macrophages counts) when compared with the ones with a successful treatment (71% vs. 47%, P = 0.017). Furthermore, patients presenting this phenotype showed decreased recurrence-free survival (log rank, P = 0.008) and a clear 2-fold increased risk of BCG treatment failure was observed in univariate analysis (hazard ratio = 2.343; 95% CI: 1.197-4.587; P = 0.013). Even when adjusted for potential confounders, such as age and therapeutic scheme, multivariate analysis revealed 2.6-fold increased risk of recurrence (hazard ratio = 2.627; 95% CI: 1.340-5.150; P = 0.005). High stroma-predominant CD163+ macrophage counts were also associated with low expression of HIF-1α in tumor areas, whereas high counts of CD163+ in the tumor presented high expression of HIF-1α in tumor nests. Conclusions: TAMs evaluation using CD163 is a good indicator of BCG treatment failure. Moreover, elevated infiltration of CD163+ macrophages, predominantly in stroma areas but not in the tumor, may be a useful indicator of BCG treatment outcome, possibly owing to its immunosuppressive phenotype. © 2014 Elsevier Inc.
Keywords: BCG immunotherapy; Bladder cancer; CD163; CD68; Tumor-associated macrophages

Primary bone marrow mesenchymal stromal cells rescue the axonal phenotype of twitcher mice - Miranda, C.O.; Teixeira, C.A.; Sousa, V.F.; Santos,TE; Liz, M.A.; Marques,AM; Pinto-Do-Ó, P.; Sousa, M.M. (Cell Transplantation, 2014)
Krabbe's disease (KD) is a demyelinating disorder caused by the deficiency of lysosomal galactocerebrosidase (GALC), affecting both the central (CNS) and the peripheral nervous system (PNS). A current therapy, hematopoietic stem cell transplantation (HSCT), is ineffective at correcting the PNS pathology. We have previously shown that systemic delivery of immortalized bone marrow-derived murine mesenchymal stromal cells (BM-MSCs) diminishes the neuropathology of transplanted Twitcher mice, a murine model of KD. In this study, to move one step closer to clinical application, the effectiveness of a systematic delivery of primary BM-MSCs to promote recovery of the Twitcher PNS was assessed. Primary BM-MSCs grafted to the Twitcher sciatic nerve led to increased GALC activity that was not correlated to decreased psychosine (the toxic GALC substrate) accumulation. Nevertheless, BM-MSC transplantation rescued the axonal phenotype of Twitcher mice in the sciatic nerve, with an increased density of both myelinated and unmyelinated axons in transplanted animals. Whereas no increase in myelination was observed, upon transplantation an increased proliferation of Schwann cell precursors occurred. Supporting these findings, in vitro, BM-MSCs promoted neurite outgrowth of Twitcher sensory neurons and proliferation of Twitcher Schwann cells. Moreover, BM-MSCs expressed nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) and promoted increased BDNF synthesis by neighboring Schwann cells. Besides their action in neurons and glia, BM-MSCs led to macrophage activation in Twitcher sciatic nerves. In summary, primary BM-MSCs diminish the neuropathology of Twitcher sciatic nerves by coordinately affecting neurons, glia, and macrophages. © 2014 Cognizant Comm. Corp.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: Axonal degeneration; Bone marrow-derived mesenchymal stromal cells (BM-MSCs); Krabbe's disease (KD); Twitcher mice

Production, characterization and biocompatibility of marine collagen matrices from an alternative and sustainable source: The sea urchin Paracentrotus lividus - Di Benedetto, C.; Barbaglio, A.; Martinello, T.; Alongi, V.; Fassini, D.; Cullorà, E.; Patruno, M.; Bonasoro, F.; Barbosa, M.A.; Carnevali, M.D.C.; Sugni, M. (Marine Drugs, 2014)
Collagen has become a key-molecule in cell culture studies and in the tissue engineering field. Industrially, the principal sources of collagen are calf skin and bones which, however, could be associated to risks of serious disease transmission. In fact, collagen derived from alternative and riskless sources is required, and marine organisms are among the safest and recently exploited ones. Sea urchins possess a circular area of soft tissue surrounding the mouth, the peristomial membrane (PM), mainly composed by mammalian-like collagen. The PM of the edible sea urchin Paracentrotus lividus therefore represents a potential unexploited collagen source, easily obtainable as a food industry waste product. Our results demonstrate that it is possible to extract native collagen fibrils from the PM and produce suitable substrates for in vitro system. The obtained matrices appear as a homogeneous fibrillar network (mean fibril diameter 30-400 nm and < 2 μm) and display remarkable mechanical properties in term of stiffness (146 ± 48 MPa) and viscosity (60.98 ± 52.07 GPa·s). In vitro tests with horse pbMSC show a good biocompatibility in terms of overall cell growth. The obtained results indicate that the sea urchin P. lividus can be a valuable low-cost collagen source for mechanically resistant biomedical devices.
Keywords: Biocompatibility; Collagen matrix; Mesenchimal stromal cells; Native fibril; Sea urchin collagen; Tissue regeneration

Prolonged saltatory fetal heart rate pattern leading to newborn metabolic acidosis - Nunes, I.; Ayres-de-Campos, D.; Kwee, A.; Rosen, K. G. (Clinical and Experimental Obstetrics & Gynecology, 2014)

Propolis varnish: Antimicrobial properties against cariogenic bacteria, cytotoxicity, and sustained-release profile - De Luca, M.P.; Franca, J.R.; Macedo, F.A.F.F.; Grenho, L.; Cortes, M.E.; Faraco, A.A.G.; Moreira, A.N.; Santos, V.R. (BioMed Research International, 2014)
Varnishes are preparations that differ in the polymeric matrix and therapeutical agents. In dentistry they are used to prevent caries. In this study we developed a propolis varnish, considering propolis properties against cariogenic bacteria. To a chitosan polymeric base (CHV) was added ethanolic propolis extract in different concentrations: PV1 (5%), PV2 (10%), and PV3 (15%). Antimicrobial activity was carried out against Streptococcus mutans (SM), Streptococcus sanguinis (SG), Streptococcus salivarius (SS), and Lactobacillus casei (LC) through agar diffusion method. The three propolis concentrations incorporated were effective in inhibiting the growth of all microorganisms, but without significant difference between the zones of inhibition observed. Cytotoxicity assay was done by MTT method. Data were analyzed by one-way ANOVA and Bonferroni test. None of the varnishes were cytotoxic, keeping 80% of viable cells, while CHV allowed cellular proliferation (120%). Sustained-release test was carried out by applying 40 μL of each varnish in the buccal surface of bovine teeth and kept in an ethanol/water solution removed in regular times. According to the "independent model approach," the release profiles were distinct from each varnish and the most prolonged was PV3 (8 weeks). Varnish formulations had satisfactory antimicrobial activity against cariogenic bacteria and have a low cytotoxicity (<50%). © 2014 Mariana P. De Luca et al.

Quality by Design: Discussing and Assessing the Solid Dispersions Risk - Chaves, Luise L.; Vieira, Alexandre C. C.; Reis, Salette; Sarmento, Bruno; Ferreira, Domingos C. (Current Drug Delivery, 2014)

Rescue of wild-type E-cadherin expression from nonsense-mutated cancer cells by a suppressor-tRNA - Bordeira-Carriço, R.; Ferreira, D.; Mateus, D.D.; Pinheiro, H.; Pêgo, A.P.; Santos, M.A.S.; Oliveira, C. (European Journal of Human Genetics, 2014)
Hereditary diffuse gastric cancer (HDGC) syndrome, although rare, is highly penetrant at an early age, and is severe and incurable because of ineffective screening tools and therapy. Approximately 45% of HDGC families carry germline CDH1/E-cadherin alterations, 20% of which are nonsense leading to premature protein truncation. Prophylactic gastrectomy is the only recommended approach for all asymptomatic CDH1 mutation carriers. Suppressor-tRNAs can replace premature stop codons (PTCs) with a cognate amino acid, inducing readthrough and generating full-length proteins. The use of suppressor-tRNAs in HDGC patients could therefore constitute a less invasive therapeutic option for nonsense mutation carriers, delaying the development of gastric cancer. Our analysis revealed that 23/108 (21.3%) of E-cadherin-mutant families carried nonsense mutations that could be potentially corrected by eight suppressor-tRNAs, and arginine was the most frequently affected amino acid. Using site-directed mutagenesis, we developed an arginine suppressor-tRNA vector to correct one HDGC nonsense mutation. E-cadherin-deficient cell lines were transfected with plasmids carrying simultaneously the suppressor-tRNA and wild-type or mutant CDH1 mini-genes. RT-PCR, western blot, immunofluorescence, flow cytometry and proximity ligation assay (PLA) were used to establish the model, and monitor mRNA and protein expression and function recovery from CDH1 vectors. Cells expressing a CDH1 mini-gene, carrying a nonsense mutation and the suppressor-tRNA, recovered full-length E-cadherin expression and its correct localization and incorporation into the adhesion complex. This is the first demonstration of functional recovery of a mutated causative gene in hereditary cancer by cognate amino acid replacement with suppressor-tRNAs. Of the HDGC families, 21.3% are candidates for correction with suppressor-tRNAs to potentially delay cancer onset. © 2014 Macmillan Publishers Limited. All rights reserved.
Keywords: hereditary diffuse gastric cancer (HDGC); nonsense suppression; Premature termination codon (PTC); Suppressor-tRNA

Resveratrol as a Natural Anti-Tumor Necrosis Factor-alpha Molecule: Implications to Dendritic Cells and Their Crosstalk with Mesenchymal Stromal Cells - Silva, Andreia M.; Oliveira, Marta I.; Sette, Laura; Almeida, Catarina R.; Oliveira, Maria J.; Barbosa, Mario A.; Santos, Susana G. (Plos One, 2014)

Role of protein environment and bioactive polymer grafting in the S. epidermidis response to titanium alloy for biomedical applications - Vasconcelos, D.M.; Falentin-Daudré, C.; Blanquaert, D.; Thomas, D.; Granja, P.L.; Migonney, V. (Materials Science and Engineering C, 2014)
Joint implant-related infections, namely by Staphylococci, are a worldwide problem, whose consequences are dramatic. Various methods are studied to fight against these infections. Here, the proposed solution consists in grafting a bioactive polymer on joint implant surfaces in order to allow the control of the interactions with the living system. In this study, sodium styrene sulfonate, bearing sulfonate groups, was grafted on the surface of titanium alloys. Scanning Electron Microscopy, colorimetric method, Fourier-transformed infrared spectroscopy and contact angle measurements were applied to characterize the surfaces. Bacterial adhesion studies were studied on poly(sodium styrene sulfonate) grafted Ti6Al4V and Ti6Al4V surfaces previously adsorbed by proteins involved in the bacteria adhesion process. Fibrinogen and fibronectin were demonstrated to increase staphylococcal adhesion on Ti6Al4V surfaces. Ti6Al4V grafted sodium styrene sulfonate surfaces inhibited the adhesion of Staphylococcus epidermidis in 37% and 13% on pre-adsorbed surfaces with fibrinogen and fibronectin, respectively. The mechanism of the observed inhibiting bacteria adhesion properties is related to the differences of proteic conformations induced by poly(sodium styrene sulfonate) grafting.
Keywords: Bacterial adhesion; Bioactive polymer; Poly(sodium styrene sulfonate) (polyNaSS); Protein adsorption; Surface modification; Titanium alloy

Role of sparc in bone remodeling and cancer-related bone metastasis - Ribeiro, N.; Sousa, S.R.; Brekken, R.A.; Monteiro, F.J. (Journal of Cellular Biochemistry, 2014)
There is a growing socioeconomic recognition that clinical bone diseases such as bone infections, bone tumors and osteoporotic bone loss mainly associated with ageing, are major issues in today's society. SPARC (secreted protein, acidic and rich in cysteine), a matricellular glycoprotein, may be a promising therapeutic target for preventing or treating bone-related diseases. In fact, SPARC is associated with tissue remodeling, repair, development, cell turnover, bone mineralization and may also participate in growth and progression of tumors, namely cancer-related bone metastasis. Yet, the function of SPARC in such biological processes is poorly understood and controversial. The main objective of this work is to review the current knowledge related to the activity of SPARC in bone remodeling, tumorigenesis, and bone metastasis. Progress in understanding SPARC biology may provide novel strategies for bone regeneration and the development of anti-angiogenic, anti-proliferative, or counter-adhesive treatments specifically against bone metastasis. © 2013 Wiley Periodicals, Inc. © 2013 Wiley Periodicals, Inc.
Keywords: BONE METASTASIS; bone remodeling; SPARC; TUMORIGENESIS

Sca-1+cardiac progenitor cells and heart-making: A critical synopsis - Valente, M.; Nascimento, D.S.; Cumano, A.; Pinto-Do-Ó, P. (Stem Cells and Development, 2014)
The identification, in the adult, of cardiomyocyte turnover events and of cardiac progenitor cells (CPCs) has revolutionized the field of cardiovascular medicine. However, the low rate of CPCs differentiation events reported both in vitro and in vivo, even after injury, raised concerns on the biological significance of these subsets. In this Comprehensive Review, we discuss the current understanding of cardiac Lin-Sca-1+cells in light of what is also known for cellular compartments with similar phenotypes in other organs. The Lin-Sca-1+heart subset is heterogeneous and displays a mesenchymal profile, characterized by a limited ability to generate cardiomyocytes in vitro and in vivo, even after injury. There is no evidence for Sca-1 expression in embryonic cardiovascular progenitors. In other organs, Sca-1 expression is mainly observed on mesoderm-derived cells, although it is not restricted to stem/progenitor cell populations. It is urgent to determine, at a single cell level, to which extent cardiac Lin-Sca-1+cells overlap with the fibroblast compartment.

Selective albumin-binding surfaces modified with a thrombin-inhibiting peptide - Freitas, S.C.; Maia, S.; Figueiredo, A.C.; Gomes, P.; Pereira, P.J.B.; Barbosa, M.A.; Martins, M.C.L. (Acta Biomaterialia, 2014)
Blood-contacting medical devices have been associated with severe clinical complications, such as thrombus formation, triggered by the activation of the coagulation cascade due to the adsorption of certain plasma proteins on the surface of biomaterials. Hence, the coating of such surfaces with antithrombotic agents has been used to increase biomaterial haemocompatibility. Biomaterial-induced clotting may also be decreased by albumin adsorption from blood plasma in a selective and reversible way, since this protein is not involved in the coagulation cascade. In this context, this paper reports that the immobilization of the thrombin inhibitor D-Phe-Pro-D-Arg-D-Thr-CONH 2 (fPrt) onto nanostructured surfaces induces selective and reversible adsorption of albumin, delaying the clotting time when compared to peptide-free surfaces. fPrt, synthesized with two glycine residues attached to the N-terminus (GGfPrt), was covalently immobilized onto self-assembled monolayers (SAMs) having different ratios of carboxylate-hexa(ethylene glycol)- and tri(ethylene glycol)-terminated thiols (EG6-COOH/EG3) that were specifically designed to control GGfPrt orientation, exposure and density at the molecular level. In solution, GGfPrt was able to inactivate the enzymatic activity of thrombin and to delay plasma clotting time in a concentration-dependent way. After surface immobilization, and independently of its concentration, GGfPrt lost its selectivity to thrombin and its capacity to inhibit thrombin enzymatic activity against the chromogenic substrate n-p-tosyl-Gly-Pro-Arg-p-nitroanilide. Nevertheless, surfaces with low concentrations of GGfPrt could delay the capacity of adsorbed thrombin to cleave fibrinogen. In contrast, GGfPrt immobilized in high concentrations was found to induce the procoagulant activity of the adsorbed thrombin. However, all surfaces containing GGfPrt have a plasma clotting time similar to the negative control (empty polystyrene wells), showing resistance to coagulation, which is explained by its capacity to adsorb albumin in a selective and reversible way. This work opens new perspectives to the improvement of the haemocompatibility of blood-contacting medical devices. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Albumin; Blood compatibility; Clotting; Surface modification; Thrombin

Sensory neurons and osteoblasts: Close partners in a microfluidic platform - Neto, E.; Alves, C.J.; Sousa, D.M.; Alencastre, I.S.; Lourenço, A.H.; Leitão, L.; Ryu, H.R.; Jeon, N.L.; Fernandes, R.; Aguiar, P.; Almeida, R.D.; Lamghari, M. (Integrative Biology (United Kingdom), 2014)
Innervation has proven to be critical in bone homeostasis/regeneration due to the effect of soluble factors, produced by nerve fibers, associated with changes in the activity of bone cells. Thus, in this study, we have established and characterized a coculture system comprising sensory neurons and osteoblasts to mimic the in vivo scenario where nerve fibers can be found in a bone microenvironment. Embryonic or adult primary dorsal root ganglion (DRG) and MC3T3-E1 osteoblastic cells were cocultured in compartmentalized microfluidic platforms and morphological and functional tests were performed. The time of adhesion and readout of axonal outgrowth were improved by the alignment of DRG with the axis of microgrooves, which showed to be a crucial step for the designed experiments. Cocultures of entire DRG from adult origin with osteoblasts were performed, showing extended DRG projections towards the axonal compartment, reaching osteoblastic cells. Immunocytochemistry showed that the neurites present within the osteoblastic compartment were immunoreactive to synapsin and calcitonin gene-related peptide suggesting the presence of specialized structures involved in this crosstalk. This evidence was further confirmed by electron microscopy where varicosities were detected as well as electron dense structures in neurite membranes. Aiming to mimic the properties of tissue extracellular matrices, MC3T3-E1 cells were seeded in the axonal side upon laminin, collagen or within 3D functionalized alginate matrices and axonal outgrowth was clearly observed. In order to analyze and quantify data with reproducible image analysis, a semi-automated algorithm was also developed. The collagen and laminin substrates displayed a higher amount of axons reaching the axonal side. Overall, the established method revealed to be a suitable tool to study the interaction between the peripheral nervous system and bone cells in different contexts mimicking the in vivo scenario. © 2014 the Partner Organisations 2014.
Cited By (since 1996):2Export Date: 21 November 2014

Splice-correcting oligonucleotides restore BTK function in X-linked agammaglobulinemia model - Bestas, B.; Moreno, P.M.D.; Blomberg, K. E. M.; Mohammad, D. K.; Saleh, A. F.; Sutlu, T.; Nordin, J. Z.; Guterstam, P.; Gustafsson, M. O.; Kharazi, S.; Piatosa, B.; Roberts, T. C.; et al. (Journal of Clinical Investigation, 2014)
Bestas, Burcu Moreno, Pedro M. D. Blomberg, K. Emelie M. Mohammad, Dara K. Saleh, Amer F. Sutlu, Tolga Nordin, Joel Z. Guterstam, Peter Gustafsson, Manuela O. Kharazi, Shabnam Piatosa, Barbara Roberts, Thomas C. Behlke, Mark A. Wood, Matthew J. A. Gait, Michael J. Lundin, Karin E. El Andaloussi, Samir Mansson, Robert Berglof, Anna Wengel, Jesper Smith, C. I. Edvard

Stability study perspective of the effect of freeze-drying using cryoprotectants on the structure of insulin loaded into PLGA nanoparticles - Fonte, P.; Soares, S.; Sousa, F.; Costa, A.; Seabra, V.; Reis, S.; Sarmento, B. (Biomacromolecules, 2014)
This work aimed to evaluate the influence of a freeze-drying process using different cryoprotectants on the structure of insulin loaded into poly(lactic-co-glycolic acid) (PLGA) nanoparticles and to assess the stability of these nanoparticles upon 6 months of storage following ICH guidelines. Insulin-loaded PLGA nanoparticles with a size around 450 nm were dehydrated using a standard freeze-drying cycle, using trehalose, glucose, sucrose, fructose, and sorbitol at 10% (w/v) as cryoprotectants. All formulations, except those nonadded of cryoprotectant and added with trehalose, collapsed after freeze-drying. The addition of cryoprotectants increased the nanoparticles stability upon storage. FTIR results showed that insulin maintained its structure after encapsulation in about 88%, decreasing to 71% after freeze-drying. The addition of cryoprotectants prior to freeze-drying increased insulin structural stability an average of up to 79%. Formulations collapsed after freeze-drying showed better protein stabilization upon storage, in special sorbitol added formulation, preserving 76, 80, and 78% of insulin structure at 4 °C, 25 °C/60% RH, and 40 °C/75% RH, respectively. Principal component analysis also showed that the sorbitol-added formulation showed the most similar insulin structural modifications among the tested storage conditions. These findings suggested that regarding nanoparticles stability, cryoprotectants are versatile to be used in a standard freeze-drying, however they present different performances on the stabilization of the loaded protein. Thus, on the freeze-drying of the nanoparticles field, this work gives rise to the importance of the process of optimization, searching for a balance between a good obtainable cake with an optimal structural stabilization of the loaded protein.

Stable phenotype and function of immortalized Lin-Sca-1 + cardiac progenitor cells in long-term culture: A step closer to standardization - Freire, AG; Nascimento, D.S.; Forte, G.; Valente, M.; Resende, TP; Pagliari, S.; Abreu, C; Carvalho, I; Nardo, P.D.; Pinto-Do-Ó, P. (Stem Cells and Development, 2014)
Putative cardiac progenitor cells (CPCs) have been identified in the myocardium and are regarded as promising candidates for cardiac cell-based therapies. Although two distinct populations of CPCs reached the clinical setting, more detailed studies are required to portray the optimal cell type and therapeutic setting to drive robust cell engraftment and cardiomyogenesis after injury. Owing to the scarcity of the CPCs and the need for reproducibility, the generation of faithful cellular models would facilitate this scrutiny. Here, we evaluate whether immortalized Lin-Sca-1+ CPCs (iCPC Sca-1) represent their native-cell counterpart, thereby constituting a robust in vitro model system for standardized investigation in the cardiac field. iCPCSca-1 were established in vitro as plastic adherent cells endowed with robust self-renewal capacity while preserving a stable phenotype in long-term culture. iCPCSca-1 differentiated into cardiomyocytic-, endothelial-, and smooth muscle-like cells when subjected to appropriate stimuli. The cell line consistently displayed features of Lin -Sca-1+ CPCs in vitro, as well as in vivo after intramyocardial delivery in the onset of myocardial infarction (MI). Transplanted iCPCSca-1 significantly attenuated the functional and anatomical alterations caused by MI while promoting neovascularization. iCPCSca-1 are further shown to engraft, establish functional connections, and differentiate in loco into cardiomyocyte- and vasculature-like cells. These data validate iCPCSca-1 as an in vitro model system for Lin-Sca-1+ progenitors and for systematic dissection of mechanisms underlying CPC subsets engraftment/differentiation in vivo. Moreover, iCPCSca-1 can be regarded as a ready-to-use CPCs source for pre-clinical bioengineering studies toward the development of novel strategies for restoration of the damaged myocardium. © Copyright 2014, Mary Ann Liebert, Inc. 2014.
Cited By (since 1996):2Export Date: 21 November 2014

Study of the isoflavone content of different extracts of Medicago spp. as potential active ingredient - Rodrigues, F.; Almeida, I.; Sarmento, B.; Amaral, M.H.; Oliveira, M.B.P.P. (Industrial Crops and Products, 2014)
This study focuses on the isoflavones composition of different extracts of Medicago species (M. minima, M. tornata, M. truncatula, M. rigidula, M. scutelata, M. segitalis and M. sativa), a leguminous crop used as animal feeding. There are some research studies on the isoflavones composition of Medicago sativa, but no comprehensive profile of isoflavones has been reported for these other six species. In this work, two glycosides (daidzin and genistin) and six aglycones (daidzein, glycitein, genistein, formononetin, prunetin and biochanin A) were determined by high performance liquid chromatography (HPLC/DAD) in three different extracts of these species: aqueous, hydroalcoholic and alcoholic. In all samples genistin, daidzein and genistein were the most abundant isoflavone compounds. The highest concentration of genistin was observed in the extracts of M. scutelata (5.2 and 9.6. mg/kg. db, respectively, for hydroalcoholic and alcoholic extract), in amounts 2-4.5-fold higher than the other samples evaluated. Daidzein is also present in high amounts in M. scutelata (19.2. mg/kg. db, alcoholic extract). Genistein is detected in several species at concentrations ranging from 0.7 (aqueous extract of M. tornata) to 16.1. mg/kg. db (alcoholic extract of M. scutelata). In terms of total isoflavones content per species, results showed significant differences between M. rigidula and M. sativa, considering all type of solvents, being the highest and the lowest one, respectively. In a general way, the extractability of compounds significantly increased from aqueous to alcoholic extracts. The study demonstrates that some Medicago species possess an excellent potential as a source of these health promoting bioactive compounds. © 2014 Elsevier B.V.
Keywords: By-product; Daidzein; Genistein; Genistin; Isoflavones; Medicago

Therapeutic antisense oligonucleotides against cancer: hurdling to the clinic - Moreno, Pedro M. D.; Pego, Ana P. (Frontiers in chemistry, 2014)
25353019

Timing embryo segmentation: Dynamics and regulatory mechanisms of the vertebrate segmentation clock - Resende, TP; Andrade, R.P.; Palmeirim, I. (BioMed Research International, 2014)
All vertebrate species present a segmented body, easily observed in the vertebrate column and its associated components, which provides a high degree of motility to the adult body and efficient protection of the internal organs. The sequential formation of the segmented precursors of the vertebral column during embryonic development, the somites, is governed by an oscillating genetic network, the somitogenesis molecular clock. Herein, we provide an overview of the molecular clock operating during somite formation and its underlying molecular regulatory mechanisms. Human congenital vertebral malformations have been associated with perturbations in these oscillatory mechanisms. Thus, a better comprehension of the molecular mechanisms regulating somite formation is required in order to fully understand the origin of human skeletal malformations. © 2014 Tatiana P. Resende et al.

Tools for address georeferencing - limitations and opportunities every public health professional should be aware of - Ribeiro, Ana Isabel; Olhero, Andreia; Teixeira, Hugo; Magalhaes, Alexandre; Pina, Maria Fatima (PloS one, 2014)

Translating chitosan to clinical delivery of nucleic acid-based drugs - Gomes, C.P.; Lopes, C.D.F.; Moreno, P.M.D.; Varela-Moreira, A.; Alonso, M.J.; Pego, A. P. (Mrs Bulletin, 2014)
Gomes, Carla Pereira Ferreira Lopes, Catia Daniela Duarte Moreno, Pedro Miguel Varela-Moreira, Aida Jose Alonso, Maria Pego, Ana PaulaPego, Ana Paula/C-6942-2012; Moreno, Pedro/J-9382-2013; Lopes, Catia/O-1090-2013 Pego, Ana Paula/0000-0001-5169-328X; Moreno, Pedro/0000-0002-3773-3262; Lopes, Catia/0000-0002-7467-6498

What do Portuguese women prefer regarding vaginal products? Results from a cross-sectional web-based survey - Palmeira-de-Oliveira, R.; Duarte, P.; Palmeira-de-Oliveira, A.; Das Neves, J.; Amaral, M.H.; Breitenfeld, L.; Martinez-de-Oliveira, J. (Pharmaceutics, 2014)
Therapeutic outcomes of vaginal products depend not only on their ability to deliver drugs to or through the vagina but also on acceptability and correct use. Women’s preferences, in turn, may vary according to age and cultural backgrounds. In this work, an anonymous online survey was completed by 2529 Portuguese women to assess their preferences for physical characteristics and mode of application of vaginal products, according to age. Additionally, intention to use and misconceptions about these issues were assessed. The majority of women of all age groups would use vaginal products to treat or prevent diseases, upon medical prescription. Women preferred vaginal products to be odorless and colorless gels, creams and ointments composed by natural origin drugs/excipients and applied by means of an applicator. Although the majority of women would prefer not to insert any product in the vagina, intention to use for self and recommendation to use for others was associated with previous experiences with vaginal products. General concerns and misconceptions related to use of vaginal products were rare. These data may contribute to the development of products that women are more prone to use.
Keywords: Acceptability; Vaginal dosage forms; Vaginal products; Women’s preferences

What do portuguese women prefer regarding vaginal products? Results from a cross-sectional web-based survey - Palmeira-de-Oliveira, Rita; Duarte, Paulo; Palmeira-de-Oliveira, Ana; das Neves, Jose; Amaral, Maria Helena; Breitenfeld, Luiza; Martinez-de-Oliveira, Jose (Pharmaceutics, 2014)
25337676

Adsorbed fibrinogen leads to improved bone regeneration and correlates with differences in the systemic immune response - Santos, S.G.; Lamghari, M.; Almeida, C.R.; Oliveira, M.I.; Neves, N.; Ribeiro, A.C.; Barbosa, J.N.; Barros, R.; Maciel, J.; Martins, M.C.L.; Gonçalves, R.M.; Barbosa, M.A. (Acta Biomaterialia, 2013)

Adult stem cells and biocompatible scaffolds as smart drug delivery tools for cardiac tissue repair - Pagliari, S.; Romanazzo, S.; Mosqueira, D.; Pinto-Do-Ó, P.; Aoyagi, T.; Forte, G. (Current Medicinal Chemistry, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Advanced biofabrication strategies for skin regeneration and repair - Pereira, R.F.; Barrias, C.C.; Granja, P.L.; Bartolo, P.J. (Nanomedicine, 2013)
Cited By (since 1996):3Export Date: 12 December 2013Source: Scopus

An overview of central fetal monitoring systems in labour - Nunes, Inês; Ayres-de-Campos, Diogo; Figueiredo, Catarina; Bernardes, João %@ 1619-3997 (2013)

Assessing the physical-chemical properties and stability of dapivirine-loaded polymeric nanoparticles - Das Neves, J.; Amiji, M.; Bahia, M.F.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Automatic lane segmentation in TLC images using the continuous wavelet transform - Moreira, B.; Sousa, A.; Mendonça, A.M.; Campilho, A. (Computational and Mathematical Methods in Medicine, 2013)

Automatic localization of the optic disc by combining vascular and intensity information - Mendonça, A.M.; Sousa, A.; Mendonça, L.; Campilho, A. (Computerized Medical Imaging and Graphics, 2013)

Bacterial-binding chitosan microspheres for gastric infection treatment and prevention - Gonçalves, I.C.; Magalhães, A.; Fernandes, M.; Rodrigues, I.V.; Reis, C.A.; Martins, M.C.L. (Acta Biomaterialia, 2013)

Biocompatibility of poly(lactic acid) with incorporated graphene-based materials - Pinto, A.M.; Moreira, S.; Gonçalves, I.C.; Gama, F.M.; Mendes, A.M.; Magalhães, F.D. (Colloids and Surfaces B: Biointerfaces, 2013)
Cited By (since 1996):3Export Date: 12 December 2013Source: Scopus

Bioengineered surfaces promote specific protein-glycan mediated binding of the gastric pathogen Helicobacter pylori - Parreira, P.; Magalhães, A.; Reis, C.A.; Borén, T.; Leckband, D.; Martins, M.C.L. (Acta Biomaterialia, 2013)

Brain targeting effect of camptothecin-loaded solid lipid nanoparticles in rat after intravenous administration - Martins, S.M.; Sarmento, B.; Nunes, C.; Lúcio, M.; Reis, S.; Ferreira, D.C. (European Journal of Pharmaceutics and Biopharmaceutics, 2013)

Cetuximab conjugated O-carboxymethyl chitosan nanoparticles for targeting EGFR overexpressing cancer cells - Maya, S.; Kumar, L.G.; Sarmento, B.; Sanoj Rejinold, N.; Menon, D.; Nair, S.V.; Jayakumar, R. (Carbohydrate Polymers, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Characterization of human NLZ1/ZNF703 identifies conserved domains essential for proper subcellular localization and transcriptional repression - Pereira-Castro, I.; Costa, Â.M.S.; Oliveira, M.J.; Barbosa, I.; Rocha, A.S.; Azevedo, L.; Da Costa, L.T. (Journal of Cellular Biochemistry, 2013)

Co-expression network analysis and genetic algorithms for gene prioritization in preeclampsia - Tejera, E.; Bernardes, J.; Rebelo, I. (BMC Medical Genomics, 2013)

Comparison of different methods of heart rate entropy analysis during acute anoxia superimposed on a chronic rat model of pulmonary hypertension - Gonçalves, H.; Henriques-Coelho, T.; Rocha, A.P.; Lourenço, A.P.; Leite-Moreira, A.; Bernardes, J. (Medical Engineering and Physics, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Comparison of real beat-to-beat signals with commercially available 4 Hz sampling on the evaluation of foetal heart rate variability - Gonçalves, H.; Costa, A.; Ayres-de-Campos, D.; Costa-Santos, C.; Rocha, A.P.; Bernardes, J. (Medical and Biological Engineering and Computing, 2013)

Could moderate earthquakes also trigger cardiac events? - Ribeiro, A.I.; De Fátima De Pina, M. (European Journal of Epidemiology, 2013)

Development and validation method for simultaneous quantification of phenolic compounds in natural extracts and nanosystems - Da Silva, S.B.; Oliveira, A.; Ferreira, D.; Sarmento, B.; Pintado, M. (Phytochemical Analysis, 2013)

Development of bis-locked nucleic acid (bisLNA) oligonucleotides for efficient invasion of supercoiled duplex DNA - Moreno, P.M.D.; Geny, S.; Pabon, Y.V.; Bergquist, H.; Zaghloul, E.M.; Rocha, C.S.J.; Oprea, I.I.; Bestas, B.; Andaloussi, S.E.; Jørgensen, P.T.; Pedersen, E.B.; Lundin, K.E.; et al. (Nucleic Acids Research, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

Development of PLGA-mannosamine nanoparticles as oral protein carriers - Alonso-Sande, M.; Des Rieux, A.; Fievez, V.; Sarmento, B.; Delgado, A.; Evora, C.; Remuñán-López, C.; Préat, V.; Alonso, M.J. (Biomacromolecules, 2013)

E-cadherin and adherens-junctions stability in gastric carcinoma: Functional implications of glycosyltransferases involving N-glycan branching biosynthesis, N-acetylglucosaminyltransferases III and v - Pinho, S.S.; Figueiredo, J.; Cabral, J.; Carvalho, S.; Dourado, J.; Magalhães, A.; Gärtner, F.; Mendonça, A.M.; Isaji, T.; Gu, J.; Carneiro, F.; Seruca, R.; et al. (Biochimica et Biophysica Acta - General Subjects, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Effect of freeze-drying, cryoprotectants and storage conditions on the stability of secondary structure of insulin-loaded solid lipid nanoparticles - Soares, S.; Fonte, P.; Costa, A.; Andrade, J.; Seabra, V.; Ferreira, D.; Reis, S.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Effect of gastric environment on Helicobacter pylori adhesion to a mucoadhesive polymer - Nogueira, F.; Gonçalves, I.C.; Martins, M.C.L. (Acta Biomaterialia, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

Effects of density of anisotropic microstamped silica thin films on guided bone tissue regeneration - In vitro study - Pelaez-Vargas, A.; Gallego-Perez, D.; Carvalho, A.; Fernandes, M.H.; Hansford, D.J.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part B Applied Biomaterials, 2013)

Endothelialization of chitosan porous conduits via immobilization of a recombinant fibronectin fragment (rhFNIII7-10) - Amaral, I.F.; Neiva, I.; Ferreira da Silva, F.; Sousa, S.R.; Piloto, A.M.; Lopes, C.D.F.; Barbosa, M.A.; Kirkpatrick, C.J.; Pêgo, A.P. (Acta Biomaterialia, 2013)

Engineering of a 3D nanostructured scaffold made of functionalized self-assembling peptides and encapsulated neural stem cells - Cunha, C.; Panseri, S.; Gelain, F. (Methods in Molecular Biology, 2013)

Enzymatic, physicochemical and biological properties of MMP-sensitive alginate hydrogels - Fonseca, K.B.; Maia, F.R.; Cruz, F.A.; Andrade, D.; Juliano, M.A.; Granja, P.L.; Barrias, C.C. (Soft Matter, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Establishment of a triple co-culture in vitro cell models to study intestinal absorption of peptide drugs - Antunes, F.; Andrade, F.; Araújo, F.; Ferreira, D.; Sarmento, B. (European Journal of Pharmaceutics and Biopharmaceutics, 2013)
Cited By (since 1996):4Export Date: 12 December 2013Source: Scopus

Expression of ST3GAL4 Leads to SLex Expression and Induces c-Met Activation and an Invasive Phenotype in Gastric Carcinoma Cells - Gomes, C.; Osório, H.; Pinto, M.T.; Campos, D.; Oliveira, M.J.; Reis, C.A. (PLoS ONE, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: ScopusArt. No.: e66737

Fibrinogen promotes resorption of chitosan by human osteoclasts - Torres, A.L.; Santos, S.G.; Oliveira, M.I.; Barbosa, M.A. (Acta Biomaterialia, 2013)

Functionalization of biomaterials with small osteoinductive moieties - Maia, F.R.; Bidarra, S.J.; Granja, P.L.; Barrias, C.C. (Acta Biomaterialia, 2013)

Gender-specific heart rate dynamics in severe intrauterine growth-restricted fetuses - Gonçalves, H.; Bernardes, J.; Ayres-de-Campos, D. (Early Human Development, 2013)

Graphene-based materials biocompatibility: A review - Pinto, A.M.; Gonçalves, I.C.; Magalhães, F.D. (Colloids and Surfaces B: Biointerfaces, 2013)

High biocompatibility and improved osteogenic potential of novel Ca-P/titania composite scaffolds designed for regeneration of load-bearing segmental bone defects - Cunha, C.; Sprio, S.; Panseri, S.; Dapporto, M.; Marcacci, M.; Tampieri, A. (Journal of Biomedical Materials Research - Part A, 2013)

Highly focalised thermotherapy using a ferrimagnetic cement in the treatment of a melanoma mouse model by low temperature hyperthermia - Portela, A.; Vasconcelos, M.; Fernandes, M.H.; Garcia, M.; Silva, A.; Gabriel, J.; Gartner, F.; Amorim, I.; Cavalheiro, J. (International Journal of Hyperthermia, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

Hyaluronic acid / chitosan multilayer coatings on neuronal implants for localized delivery of siRNA nanoplexes - Hartmann, H.; Hossfeld, S.; Schlosshauer, B.; Mittnacht, U.; Pêgo, A.P.; Dauner, M.; Doser, M.; Stoll, D.; Krastev, R. (Journal of Controlled Release, 2013)

Hydrolyzed galactomannan-modified nanoparticles and flower-like polymeric micelles for the active targeting of rifampicin to macrophages - Moretton, M.A.; Chiappetta, D.A.; Andrade, F.; Das Neves, J.; Ferreira, D.; Sarmento, B.; Sosnik, A. (Journal of Biomedical Nanotechnology, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

The importance of antimicrobial peptides and their potential for therapeutic use in ophthalmology - Silva, N.C.; Sarmento, B.; Pintado, M. (International Journal of Antimicrobial Agents, 2013)

In vitro and Ex Vivo evaluation of polymeric nanoparticles for vaginal and rectal delivery of the anti-HIV drug dapivirine - Das Neves, J.; Araújo, F.; Andrade, F.; Michiels, J.; Ariën, K.K.; Vanham, G.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Molecular Pharmaceutics, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Information-based measure of disagreement for more than two observers: A useful tool to compare the degree of observer disagreement - Henriques, T.; Antunes, L.; Bernardes, J.; Matias, M.; Sato, D.; Costa-Santos, C. (BMC Medical Research Methodology, 2013)

Keratins and lipids in ethnic hair - Cruz, C.F.; Fernandes, M.M.; Gomes, A.C.; Coderch, L.; Martí, M.; Méndez, S.; Gales, L.; Azoia, N.G.; Shimanovich, U.; Cavaco-Paulo, A. (International Journal of Cosmetic Science, 2013)
Cited By (since 1996):3Export Date: 12 December 2013Source: Scopus

Loss of WNK2 expression by promoter gene methylation occurs in adult gliomas and triggers Rac1-mediated tumour cell invasiveness - Moniz, S.; Martinho, O.; Pinto, F.; Sousa, B.; Loureiro, C.; Oliveira, M.J.; Moita, L.F.; Honavar, M.; Pinheiro, C.; Pires, M.; Lopes, J.M.; Jones, C.; et al. (Human Molecular Genetics, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: ScopusArt. No.: dds405

Macrophage polarization following chitosan implantation - Vasconcelos, D.P.; Fonseca, A.C.; Costa, M.; Amaral, I.F.; Barbosa, M.A.; Águas, A.P.; Barbosa, J.N. (Biomaterials, 2013)

Macrophages stimulate gastric and colorectal cancer invasion through EGFR Y1086, c-Src, Erk1/2 and Akt phosphorylation and smallGTPase activity - Cardoso, A.P.; Pinto, M.L.; Pinto, A.T.; Oliveira, M.I.; Pinto, M.T.; Gonçalves, R.; Relvas, J.B.; Figueiredo, C.; Seruca, R.; Mantovani, A.; Mareel, M.; Barbosa, M.A.; et al. (Oncogene, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: ScopusArticle in Press

Medicago spp. extracts as promising ingredients for skin care products - Rodrigues, F.; Palmeira-de-Oliveira, A.; Das Neves, J.; Sarmento, B.; Amaral, M.H.; Oliveira, M.B. (Industrial Crops and Products, 2013)

Minimum error entropy classification - Marques De Sá, J.P.; Silva, L.M.A.; Santos, J.M.F.; Alexandre, L.A. (Studies in Computational Intelligence, 2013)

A model for educational simulation of the effect of oxytocin on uterine contractions - Lobo, M.F.; Bastos, L.F.; van Meurs, W.L.; Ayres-de-Campos, D. (Medical Engineering and Physics, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Modulation of stability and mucoadhesive properties of chitosan microspheres for therapeutic gastric application - Fernandes, M.; Gonçalves, I.C.; Nardecchia, S.; Amaral, I.F.; Barbosa, M.A.; Martins, M.C.L. (International Journal of Pharmaceutics, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Month of birth and risk of multiple sclerosis in a Portuguese population - Barros, P.; De Sá, J.M.; Sá, M.J. (Clinical Neurology and Neurosurgery, 2013)

Nanotechnology and pulmonary delivery to overcome resistance in infectious diseases - Andrade, F.; Rafael, D.; Videira, M.; Ferreira, D.; Sosnik, A.; Sarmento, B. (Advanced Drug Delivery Reviews, 2013)

Neuropeptide y modulates fracture healing through Y1 receptor signaling - Sousa, D.M.; McDonald, M.M.; Mikulec, K.; Peacock, L.; Herzog, H.; Lamghari, M.; Little, D.G.; Baldock, P.A. (Journal of Orthopaedic Research, 2013)

A novel bioactive peptide: Assessing its activity over murine neural stem cells and its potential for neural tissue engineering - Caprini, A.; Silva, D.; Zanoni, I.; Cunha, C.; Volontè, C.; Vescovi, A.; Gelain, F. (New Biotechnology, 2013)

Novel resveratrol nanodelivery systems based on lipid nanoparticles to enhance its oral bioavailability - Neves, A.R.; Lúcio, M.; Martins, S.; Lima, J.L.C.; Reis, S. (International Journal of Nanomedicine, 2013)
Cited By (since 1996):3Export Date: 12 December 2013Source: Scopus

Osteoporotic hip fractures: Bisphosphonates sales and observed turning point in trend. A population-based retrospective study - Alves, S.M.; Economou, T.; Oliveira, C.; Ribeiro, A.I.; Neves, N.; Goméz-Barrena, E.; Pina, M.F. (Bone, 2013)

Overexpression of tumour-associated carbohydrate antigen sialyl-Tn in advanced bladder tumours - Ferreira, J.A.; Videira, P.A.; Lima, L.; Pereira, S.; Silva, M.; Carrascal, M.; Severino, P.F.; Fernandes, E.; Almeida, A.; Costa, C.; Vitorino, R.; Amaro, T.; et al. (Molecular Oncology, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

An overview of central fetal monitoring systems in labour - Nunes, I.; Ayres-de-Campos, D.; Figueiredo, C.; Bernardes, J. (Journal of Perinatal Medicine, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Physical activity-friendly neighbourhood among older adults from a medium size urban setting in Southern Europe - Ribeiro, A.I.; Mitchell, R.; Carvalho, M.S.; De Pina, M.D.F. (Preventive Medicine, 2013)

Preparation and characterization of collagen-nanohydroxyapatite biocomposite scaffolds by cryogelation method for bone tissue engineering applications - Rodrigues, S.C.; Salgado, C.L.; Sahu, A.; Garcia, M.P.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part A, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Protective effects of Lavandula viridis L'Hér extracts and rosmarinic acid against H2O2-induced oxidative damage in A172 human astrocyte cell line - Costa, P.; Sarmento, B.; Gonçalves, S.; Romano, A. (Industrial Crops and Products, 2013)

Response of monocultured and co-cultured human microvascular endothelial cells and mesenchymal stem cells to macroporous granules of nanostructured- hydroxyapatite agglomerates - Laranjeira, M.S.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Nanotechnology, 2013)

Should European perinatal indicators be revisited? - Santos, J.V.; Correia, C.; Cabral, F.; Bernardes, J.; Costa-Pereira, A.; Freitas, A. (European Journal of Obstetrics Gynecology and Reproductive Biology, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

The smart connective tissue of echinoderms: A materializing promise for biotech applications - Barbaglio, A.; Tricarico, S.; Di Benedetto, C.; Fassini, D.; Lima, A.P.; Ribeiro, A.R.; Ribeiro, C.C.; Sugni, M.; Bonasoro, F.; Wilkie, L.; Barbosa, M.; Candia Carnevali, M.D. (Cahiers de Biologie Marine, 2013)

Sociodemographic determinants of prevalence and incidence of helicobacter pylori infection in portuguese adults - Bastos, J.; Peleteiro, B.; Barros, R.; Alves, L.; Severo, M.; de Fátima Pina, M.; Pinto, H.; Carvalho, S.; Marinho, A.; Guimarães, J.T.; Azevedo, A.; La Vecchia, C.; et al. (Helicobacter, 2013)

Stable phenotype and function of immortalized Lin-Sca-1+ cardiac progenitor cells in long-term culture: a step closer to standardization. - Freire, AG; Nascimento, D.S.; Forte, G.; Valente, M.; Resende, TP; Pagliari, S.; Abreu, C; Carvalho, I; Di Nardo, P.; Pinto-Do-Ó, P. (Stem Cells Dev, 2013)

Taking tissue adhesives to the future: From traditional synthetic to new biomimetic approaches - Bré, L.P.; Zheng, Y.; Pêgo, A.P.; Wang, W. (Biomaterials Science, 2013)
Cited By (since 1996):3Export Date: 12 December 2013Source: Scopus

Taking tissue adhesives to the future: from traditional synthetic to new biomimetic approaches - Bré, Lígia Pereira; Zheng, Yu; Pêgo, Ana Paula; Wang, Wenxin (Biomaterials Science, 2013)

Towards the characterization of an in vitro triple co-culture intestine cell model for permeability studies - Araújo, F.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Adhesion of Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa onto nanohydroxyapatite as a bone regeneration material - Grenho, L.; Manso, M.C.; Monteiro, F.J.; Ferraz, M.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2012)
In orthopedics due to the enormous number of surgical procedures involving invasive implant biomaterials, infections have a huge impact in terms of morbidity, mortality, and medical costs. In this study the initial adhesion of several strains namely Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa, to nanohydroxyapatite, previously heat-treated at 725°C and 1000°C was assessed. Adherent cells were evaluated by scanning electron microscopy and quantified by confocal laser scanning microscopy and as colony forming units after being released by sonication. The wettability and roughness of samples surfaces were assessed by contact angle measurements and atomic force microscopy, respectively. Nanohydroxyapatite heat-treated at 1000°C appeared to be more resistant to bacterial adhesion, over time, in five of the six tested strains while the clinical strains isolated from orthopedic infections presented superior ability to adhere, as well as better capacity to produce slime. The increase in materials sintering temperature resulted in increased hydrophobicity and roughness; however, other surface features such as the decrease in surface area and on porosity as well as the decrease on zeta potential may be the aspects that contributed to a lower bacterial adhesion on the materials sintered at 1000°C. © 2012 Wiley Periodicals, Inc.
Keywords: Adherent cells; Adhesion; article; Atomic force microscopy; Bacteria; Bacterial adhesion; bacterium adherence; Biocompatible Materials; Biological materials; biomaterial; Biomaterials; Bone; bone infection; Bone Regeneration; Bone regeneration materials; Clinical strains; Colony Count, Microbial; colony forming unit; Colony forming units; confocal laser microscopy; Confocal laser scanning microscopy; confocal microscopy; Contact angle; Durapatite; hydrophobicity; Microscopy, Confocal; Microscopy, Electron, Scanning; Nano-hydroxyapatite; Nanohydroxyapatite; nanoparticles; nonhuman; porosity; Pseudomonas aeruginosa; Scanning electron microscopy; Sintering; Sintering temperatures; Staphylococcus aureus; Staphylococcus epidermidis; Surface area; Surface feature; surface property; Surface roughness; Surgical procedures; temperature; ultrasound; unclassified drug; wettability; Zeta potential

Automatic assessment of Leishmania infection indexes on in vitro macrophage cell cultures - Leal, P.; Ferro, L.; Marques, M.; Romão, S.; Cruz, T.; Tomá, A.M.; Castro, H.; Quelhas, P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
Evaluation of parasite infection indexes on in vitro cell cultures is a practice commonly employed by biomedical researchers to address biological questions or to test the efficacy of novel anti-parasitic compounds. In the particular case of Leishmania infantum, a unicellular parasite that parasitizes macrophages, infection indexes are usually determined either by visual inspection of cells directly under the microscope or by counting digital images using appropriate software. In either case assessment of infection indexes is time consuming, thus motivating the creation of automatic image analysis approaches that allow large scale studies of Leishmania-infected macrophage cultures. We propose a fully automated method for automatic evaluation of parasite infection indexes through the segmentation of individual macrophages nucleus and cytoplasm, as well as the segmentation and co-localization of the parasites in the image. To perform such analysis with robustness and increased performance we propose the use of local image filters tuned to the specific size of the objects to detect, in conjunction with image segmentation approaches. The objects size estimation is then improved through a learning feedback loop. Cytoplasm is detected by seeded watershed segmentation. Our approach obtains, for 86 images from 4 experiments, an average parasite infection index evaluation error of 2.3%. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_51Language of Original Document: EnglishCorrespondence Address: Leal, P.; Universidade Do Porto, Faculdade de Engenharia, Departamento de Engenharia QuímicaPortugalReferences: Castro, H., Sousa, C., Santos, M., Cordeiro-da-Silva, A., Flohé, L., Tomás, A., Complementary antioxidant defence by cytoplasmic and mitochondrial peroxiredoxins in Leishmania infantum (2002) Free Radical Biology and Medicine, 33, pp. 1552-1562;Chen, X., Zhou, X., Wong, S., Automated segmentation, classification, and tracking of cancer cell nuclei in time-lapse microscopy IEEE Trans. on Biomedical Engineering, 53 (4), pp. 762-766; Marcuzzo, M., Quelhas, P., Campilho, A., Maria Mendonça, A., Campilho, A., Automated arabidopsis plant root cell segmentation based on svm classification and region merging (2009) Computers in Biology and Medicine, 39 (9); Chen, Y., Ladi, E., Herzmark, P., Robey, E., Roysam, B., Automated 5-d analysis of cell migration and interaction in the thymic cortex from time-lapse sequences of 3-d multi-channel multi-photon images (2009) J. Immunol. Methods, 340 (1), pp. 65-80; Esteves, T., Quelhas, P., Mendonça, A.M., Campilho, A., Gradient convergence filters and a phase congruency approach for in vivo cell nuclei detection Machine Vision and Applications, , in press; Schmitt, O., Hasse, M., Morphologic multiscale decomposition of connected regions with emphasis on cell clusters (2009) CVIU, 113 (2), pp. 188-201; Usaj, M., Torkar, D., Kanduser, M., Miklavcic, D., Cell counting tool parameters optimization approach for electroporation efficiency determination of attached cells in phase contrast image (2010) Journal of Microscopy, 241 (3), pp. 303-314; Sezgin, M., Sankur, B., Survey over image thresholding techniques and quantitative performance evaluation (2003) Journal of Electronic Imaging, 13 (1), pp. 146-165; Lowe, D., Distinctive Image Features from Scale-Invariant Keypoints (2004) International Journal of Computer Vision; Lindberg, T., Scale-space theory: A basic tool for analysing structures at different scales (1994) Journal of Applied Statistics, pp. 11-24; Yan, P., Zhou, X., Shah, M., Wong, S.T.C., Automatic segmentation of high-throughput RNAi fluorescent cellular images (2008) IEEE Trans. Inf. Technol. Biomed., 12 (1), pp. 109-117; CellNote: Plataforma para An?alise Assistida de Imagens, Bruno Afonso Da Cruz Lopes, , Master Thesis, Faculty of Sciences of the University of Porto
Keywords: Automated methods; Automatic assessment; Automatic evaluation; Automatic image analysis; Cell culture; Cell nuclei detection; cell nucleus; Colocalization; Digital image; Enzyme inhibition; Feed-back loop; Image analysis; Image filters; Image segmentation; In-vitro; Leishmania; Leishmania infantum; Macrophage cells; Macrophage culture; Macrophages; microscopy image segmentation; Microscopy images; Parasite infection; Parasite-; Size estimation; Visual inspection; Watershed segmentation

Automatic lane detection in chromatography images - Moreira, B.M.; Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This paper proposes a method for automating the detection of lanes in Thin-Layer Chromatography images. Our approach includes a preprocessing step to detect the image region of interest, followed by background estimation and removal. This image is then projected onto the horizontal direction to integrate the information into a one-dimensional profile. A smoothing filter is applied to this profile and the outcome is the input of the lane detection process, which is performed in three phases. The first one aims at obtaining an initial set of candidate lanes that are further validated or removed in the second phase. The last phase is a refinement step that allows the inclusion of lanes that are not clearly distinguishable in the profile and that were not included in the initial set. The method was evaluated in 66 chromatography images and achieved values of recall, precision and F β -measure of 97.0%, 99.4% and 98.2%, respectively. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_22Language of Original Document: EnglishCorrespondence Address: Moreira, B.M.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: moreira@fe.up.ptReferences: Fried, B., Sherma, J., (1999) Thin-Layer Chromatography, , Marcel Dekker, New York;Rodrigues, L.G., Ferraz, M.J., Rodrigues, D., Pais-Vieira, M., Lima, D., Brady, R.O., Sá-Miranda, M.C., Neurophysiological behavioral and morphological abnormalities in the Fabry knockout mice (2009) Neurobiology of Disease, 33 (1), pp. 48-56; Elstein, D., Altarescu, G., Beck, M., (2010) Fabry Disease, , Springer, Heidelberg; Houck, M.M., Siegel, J.A., (2010) Fundamentals of Forensic Science, , Elsevier, Oxford; Machado, A.M.C., Campos, M.F.M., Siqueira, A.M., De Carvalho, O.S.F., An iterative algorithm for segmenting lanes in gel electrophoresis images (1997) Proc. X Brazilian Symposium on Computer Graphics and Image Processing, pp. 140-146. , October; Elder, J.K., Southern, E.M., Computer-aided analysis of one dimensional restriction fragment gels (1987) Nucleic Acid and Protein Sequence Analysis - A Practical Aproach, pp. 165-172. , Bishop, M.J., Rawlings, C.J. (eds.) IRL Press, Oxford; Bajla, I., Holländer, I., Fluch, S., Burg, K., Kollár, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Computer Methods and Programs in Biomedicine, 77, pp. 209-231; Lin, C., Ching, Y., Yang, Y., An Automatic Method to Compare the Lanes in Gel Electrophoresis (GE) Images (2007) IEEE Transaction on Information Technology in Biomedicine, 11 (2), pp. 179-189; Akbari, A., Fritz, A., Jackobsen, K.S., Automatic lane detection and separation in one dimensional gel images using continuous wavelet transform (2010) The Royal Society of Chemistry, Analytical Methods, 2, pp. 1360-1371; Sousa, A.V., Aguiar, R.L., Mendonça, A.M., Campilho, A.C., Automatic Lane and Band Detection in Images of Thin Layer Chromatography (2004) LNCS, 3212, pp. 158-165. , Campilho, A.C., Kamel, M.S. (eds.) ICIAR 2004. Springer, Heidelberg; Sotaquira, M., On the use of distance maps in the analysis of 1D DNA gel images (2009) ICDIP 2009: Proceedings of the International Conference on Digital Image Processing, pp. 172-176. , IEEE Computer Society; Barrantes, P., Alvarado, P., Lane Detection on Gel Electrophoresis Images using Active Shape Models (2011) Proc. of the Conference on Technologies for Sustainable Development, TSD 2011, pp. 43-46. , February; Mendonça, A.M., Sousa, A.V., Sá-Miranda, M.C., Campilho, A.C., Automatic segmentation of chromatographic images for region of interest delineation (2011) Proc. SPIE, 7962, pp. 79623B1-79623B7; Chau, F., Liang, Y., Gao, J., Shao, X., (2004) Chemometrics - from Basics to Wavelet Transform, , John Wiley & Sons, New Jersey; Press, W.H., Flannery, B.P., Teukolsky, S.A., Vetterling, W.T., (1992) Numerical Recipes in C: The Art of Scientific Computing, , Syndicate of the University of Cambridge; Soille, P., Jones, C.D., Smith, A.B., Roberts, E.F., (2004) Morphological Image Analysis - Principles and Applications, , Springer; Visa, S., Ralescu, A., Learning Imbalanced and Overlapping Classes using Fuzzy Sets Workshop on Learning from Imbalanced Datasets II, ICML (2003)
Keywords: Background estimation; Bio-medical image processing; Biomedical image processing; Chromatography; Chromatography images; Computer aided diagnosis; Image analysis; Image regions; Lane detection; Pre-processing step; Refinement step; Second phase; Smoothing filters; Three phasis

Automatic localization of the optic disc in retinal images based on the entropy of vascular directions - Mendonça, A.M.; Cardoso, F.; Sousa, A.V.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This paper proposes an automatic method for estimating the location of the optic disc in color images of the retina. The proposed methodology is founded in a new concept, the entropy of vascular directions, which proved to be a reliable measure for assessing the convergence of vessels around an image point. To improve the robustness of the method, the search for the maximum value of entropy is restricted to image areas with high intensity. This new method was evaluated in two publicly available databases, containing both normal and pathological images, and was able to obtain a valid location for the optic disc in 115 out of the 121 images of the two datasets. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_50Language of Original Document: EnglishCorrespondence Address: Mendonça, A.M.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: amendon@fe.up.ptReferences: Jelinek, H., Cree, M., (2010) Automated Image Detection of Retinal Pathology, , CRC Press, Taylor & Francis Group, Boca Raton;Couper, D.J., Klein, R., Hubbard, L.D., Wong, T.Y., Sorlie, P., Cooper, L.S., Brothers, R.J., Nieto, F.J., Reliability of Retinal Photography in the Assessment of Retinal Microvascular Characteristics: The Atherosclerosis Risk in Communities Study (2002) American Journal of Ophthalmology, 133 (1), pp. 78-88; Sinthanayothin, C., Boyce, J.F., Cook, H.L., Williamson, T.H., Automated localization of the optic disc, fovea, and retinal blood vessels from digital colour fundus images (1999) Br. J. Ophthalmol., 83, pp. 902-910; Aquino, A., Gegúndez-Arias, M.E., Marin, D., Detecting the Optic Disc Boundary in Digital Fundus Images Using Morphological, Edge Detection and Feature Extraction Techniques (2010) IEEE Trans. Medical Imaging, 29 (11), pp. 1860-1869; Aquino, A., Gegúndez-Arias, M.E., Marin, D., Automated Optic Disc Detection in Retinal Images of Patients with Diabetic Retinopathy and Risk of Macular Edema (2012) Int. J. of Biological and Life Sciences, 8 (2), pp. 87-92; Lalonde, M., Beaulieu, M., Gagnon, L., Fast and Robust Optic Disc Detection Using Pyramidal Decomposition and Hausdorff-based Template Matching (2001) IEEE Trans. Medical Imaging, 20 (11), pp. 1193-1200; Osareh, A., Mirmehdi, M., Thomas, B., Markham, R., Classification and Localisation of Diabetic-Related Eye Disease (2002) LNCS, 2353, pp. 502-516. , Heyden, A., Sparr, G., Nielsen, M., Johansen, P. (eds.) ECCV 2002. Springer, Heidelberg; Lowell, J., Hunter, A., Steel, D., Basu, A., Ryder, R., Fletcher, E., Kennedy, L., Optic Nerve head Segmentation (2004) IEEE Trans. Medical Imaging, 23 (2), pp. 256-264; Abdel-Ghafar, R.A., Morris, T., Progress towards automated detection and characterization of the optic disc in glaucoma and diabetic retinopathy (2007) Medical Informatics and the Internet in Medicine, 32 (1), pp. 19-25; Hoover, A., Glodbaum, M., Locating the Optic Nerve in a Retinal Image Using the Fuzzy Convergence of the Blood Vessels (2003) IEEE Trans. Medical Imaging, 22 (8), pp. 951-958; Foracchia, M., Grisan, E., Ruggeri, A., Detection of Optic Disc in Retinal Images by Means of a Geometrical Model of Vessel Structure (2004) IEEE Trans. Medical Imaging, 23 (10), pp. 1189-1195; Haar, F., (2005) Automatic Localization of the Optic Disc in Digital Colour Images of the Human Retina, , Msc Thesis, University of Utrecht; Youssif, A., Ghalwash, A.Z., Ghoneim, A., Optic Disc Detection from Normalized Digital Fundus Images by Means of a Vessels' Direction Matched Filter (2008) IEEE Trans. Medical Imaging, 27 (1), pp. 11-18; Niemeijer, M., Abràmoff, M.D., Van Ginneken, B., Fast detection of the optic disc and fovea in color fundus photographs (2009) Medical Image Analysis, 13, pp. 859-870; Xu, X., Gravin, M.K., Abràmoff, M.D., Reinhardt, J.M., Simultaneous Automatic Detection of the Optic Disc and Fovea on Fundus Photographs (2011) Proc. SPIE Medical Imaging 2011: Image Processing, 7962, pp. 7962T. , Dawant, B.M., Haynor, D.R. (eds.) SPIE; http://www.isi.uu.nl/Research/Databases/DRIVEhttp://www.ces.clemson.edu/~ahoover/stare, The STARE projectMendonça, A., Campilho, A., Segmentation of Retinal Blood Vessels by Combining the Detection of Centerlines and Morphological Reconstruction (2006) IEEE Trans. Medical Imaging, 25 (9), pp. 1200-1213; Chaudhuri, S., Chattererjee, S., Katz, N., Glodbaum, M., Detection of blood Vessels in Retinal Images using Two-Dimensional Matched Filters (1989) IEEE Trans. Medical Imaging, 28 (3), pp. 263-269
Keywords: Automatic localization; Automatic method; Color images; Data sets; entropy; High intensity; Image analysis; Image points; Maximum values; Ophthalmology; optic disc; Pathological images; Retinal image; Retinal image analysis; vessel segmentation

Automatic myocardial infarction size extraction in an experimental murine model using an anatomical model - Esteves, T.; Valente, M.; Nascimento, D.S.; Pinto-Do-Ó, P.; Quelhas, P. (Proceedings - International Symposium on Biomedical ImagingIEEE Comput. Soc. Conf. Comput. Vis. Pattern Recogn., 2012)
Experimental rodent models of induced ischemic injury have been extensively used in biomedical research to study molecular, cellular and histological alterations following myocar-dial infarction. These models are increasingly employed to assess the potential of newly developed therapies for functional restoration of the damaged heart. Such studies are based on myocardial infarction induction followed by different therapeutic interventions and subsequent analysis of the infarct size. This analysis is used to evaluate the extent to which such interventions meet recovery of the lost myocardial tissue. Infarct size is defined as the percentage of the left ventricle affected by coronary artery occlusion. The infarct size is traditionally estimated manually delineating the infarcted and normal tissue areas in the left ventricle of the excised heart. However, this is a time-consuming, arduous and prone to bias process. Herein, we developed an anatomic model, adapted through expectation maximization, which allows for fully automatic analysis of the data. Experimental validation is performed comparing the proposed approach with manual annotation. The results obtained through anatomical model adaptation were coherent with those manually obtained and the differences where never higher than 10%. © 2012 IEEE.
Conference code: 91746Export Date: 21 November 2012Source: ScopusArt. No.: 6235546doi: 10.1109/ISBI.2012.6235546Language of Original Document: EnglishCorrespondence Address: Esteves, T.; Departamento de Engenharia Electrotécnica e de Computadores, Faculdade de Engenharia, Universidade Do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, PortugalReferences: Degabriele, N., Griesenbach, U., Sato, K., Critical appraisal of the mouse model of myocardial infarction (2004) Experimental Physiology, 89 (4), pp. 497-505;Lutgens, E., Daemen, M., Muinck, E., Chronic myocardial infarction in the mouse: Cardiac structural and functional changes (1998) Cardiovascular Research, 41, pp. 586-593; Takagawa, J., Zhang, Y., Wong, M., Myocardial infarct size measurement in the mouse chronic infarction model: Comparison of area- and length-based approaches (2007) Journal of Applied Physiology, 102, pp. 2104-2111; Nascimento, D., Valente, M., Esteves, T., Pina, M.F., Guedes, J.G., Freire, A., Quelhas, P., Pinto-Do, O.P., Miquant - Semi-automation of infarct size assessment in models of cardiac ischemic injury (2011) Plos One, 6 (9), pp. 1-8; Esteves, T., Valente, M., Nascimento, D., Pinto-Do, O.P., Quelhas, P., Automatic and semi-automatic analysis of the extension of myocardial infarction in an experimental murine model (2011) Proceedings of IbPRIA, LNCS, 6669, pp. 151-158; Pfeffer, M., Pfeffer, J., Fishbein, M., Myocardial infarct size and ventricular function in rats (1979) Circulation Research, 44, pp. 503-512 Sponsors: The Institute of Electrical and Electronic Engineers; Engineering in Medicine and Biology Society; Signal Processing Society
Keywords: Anatomic models; anatomical model; Anatomical models; Automatic analysis; Biomedical research; Coronary arteries; expectation maximization; Experimental validations; Image segmentation; Infarct size; Ischemic injuries; Left ventricles; Manual annotation; Maximum principle; Medical imaging; Murine model; Myocardial Infarction; Myocardial infarction size; Myocardial tissue; Normal tissue; Rodent models; Therapeutic intervention; Tissue

Automatic myocardial infarction size extraction in an experimental murine model using an anatomical model - Esteves, T.; Valente, M.; Nascimento, D.S.; Pinto-Do-Ó, P.; Quelhas, P. (Proceedings - International Symposium on Biomedical Imaging, 2012)

Bioengineered surfaces to improve the blood compatibility of biomaterials through direct thrombin inactivation - Freitas, S.C.; Cereija, T.B.; Figueiredo, A.C.; Osório, H.; Pereira, P.J.B.; Barbosa, M.A.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2012)
Thrombus formation, due to thrombin generation, is a major problem affecting blood-contacting medical devices. This work aimed to develop a new strategy to improve the hemocompatibility of such devices by the immobilization of a naturally occurring thrombin inhibitor into a nanostructured surface. Boophilin, a direct thrombin inhibitor from the cattle tick Rhipicephalus microplus, was produced as a recombinant protein in Pichia pastoris. Boophilin was biotinylated and immobilized on biotin-terminated self-assembled monolayers (SAM) via neutravidin. In order to maintain its proteinase inhibitory capacity after surface immobilization, boophilin was biotinylated after the formation of a boophilin-thrombin complex to minimize the biotinylation of the residues involved in thrombin-boophilin interaction. The extent of boophilin biotinylation was determined using matrix-assisted laser desorption/ionization-time of flight/time of flight mass spectrometry. Boophilin immobilization and thrombin adsorption were quantified using quartz crystal microbalance with dissipation. Thrombin competitive adsorption from human serum was assessed using 125I-thrombin. Thrombin inhibition and plasma clotting time were determined using spectrophotometric techniques. Boophilin-coated SAM were able to promote thrombin adsorption in a selective way, inhibiting most of its activity and delaying plasma coagulation in comparison with boophilin-free surfaces, demonstrating boophilin's potential to improve the hemocompatibility of biomaterials used in the production of blood-contacting devices. © 2012 Acta Materialia Inc.
Keywords: Coagulation; Hemocompatibility; Protein adsorption; Surface functionalization; Thrombin

Biosynthesis of highly pure poly-γ-glutamic acid for biomedical applications - Pereira, C.L.; Antunes, J.C.; Gonçalves, R.M.; Ferreira-da-Silva, F.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2012)
The remarkable properties of poly-aminoacids, mainly their biocompatibility and biodegradability, have prompted an increasing interest in these polymers for biomedical applications. Poly-γ-glutamic acid (γ-PGA) is one of the most interesting poly-aminoacids with potential applications as a biomaterial. Here we describe the production and characterization of γ-PGA by Bacillus subtilis natto. The γ-PGA was produced with low molecular weight (10-50 kDa), high purity grade (>99 %) and a D-/L-glutamate ratio of 50-60/50-40 %. To evaluate the feasibility of using this γ-PGA as a biomaterial, chitosan (Ch)/γ-PGA nanoparticles were prepared by the coacervation method at pH ranging from 3.0 to 5.0, with dimensions in the interval 214-221 nm with a poly-dispersion index of ca. 0.2. The high purity of γ-PGA produced by this method, which is firstly described here, renders this biopolymer suitable for biomedical applications. Moreover, the Ch/γ-PGA nanocomplexes developed in this investigation can be combined with biologically active substances for their delivery in the organism. The fact that the assembly between Ch and γ-PGA relies on electrostatic interactions enables addition of other molecules that can be released into the medium through changes from acidic to physiological pH, without loss in biological activity. © Springer Science+Business Media, LLC 2012.
Keywords: Amino acids; animal cell; article; Bacillus subtilis; Bacillus subtilis natto; Bioactivity; Biocompatibility; Biocompatible Materials; biodegradability; Biodegradable polymers; Biodegradation; Biologically active substances; biomaterial; Biomedical applications; biomedicine; biosynthesis; chitosan; circular dichroism; complex formation; controlled study; dispersion; Electrophoresis, Polyacrylamide Gel; feasibility study; Functional polymers; gamma polyglutamic acid; Glutamic acid; High purity; Low molecular weight; Medical applications; molecular interaction; molecular weight; Nanocomplexes; nanoparticle; nonhuman; pH; Physiological pH; polyglutamic acid; Potential applications; priority journal; purification; Spectroscopy, Fourier Transform Infrared; static electricity; Stereoisomerism; unclassified drug

Brain delivery of camptothecin by means of solid lipid nanoparticles: Formulation design, in vitro and in vivo studies - Martins, S.; Tho, I.; Reimold, I.; Fricker, G.; Souto, E.; Ferreira, D.; Brandl, M. (International Journal of PharmaceuticsInt. J. Pharm., 2012)
For the purpose of brain delivery upon intravenous injection, formulations of camptothecin-loaded solid lipid nanoparticles (SLN), prepared by hot high pressure homogenisation, were designed. Incorporation of camptothecin in the hydrophobic and acidic environment of SLN matrix was chosen to stabilise the lactone ring, which is essential for its antitumour activity, and for avoiding premature loss of drug on the way to target camptothecin to the brain.A multivariate approach was used to assess the influence of the qualitative and quantitative composition on the physicochemical properties of camptothecin-loaded SLN in comparison to plain SLN. Mean particle sizes of ≤200. nm, homogenous size distributions and high encapsulation efficiencies (>90%) were achieved for the most suitable formulations. In vitro release studies in plasma, showed a prolonged release profile of camptothecin from SLN, confirming the physical stability of the particles under physiological pH. A higher affinity of the SLN to the porcine brain capillary endothelial cells (BCEC) was shown in comparison to macrophages. MTT studies in BCEC revealed a moderate decrease in the cell viability of camptothecin, when incorporated in SLN compared to free camptothecin in solution. In vivo studies in rats showed that fluorescently labelled SLN were detected in the brain after i.v. administration. This study indicates that the camptothecin-loaded SLN are a promising drug brain delivery system worth to explore further for brain tumour therapy. © 2012 Elsevier B.V.
Keywords: Brain capillary endothelial cells (BCEC); Brain delivery; Camptothecin; Multivariate analysis; Solid lipid nanoparticles (SLN); Surfactants

Cancer syndromes and therapy by stop-codon readthrough - Bordeira-Carriço, R.; Pêgo, A.P.; Santos, M.; Oliveira, C. (Trends in Molecular MedicineTrends Mol. Med., 2012)
Several hereditary cancer syndromes are associated with nonsense mutations that create premature termination codons (PTC). Therapeutic strategies involving readthrough induction partially restore expression of proteins with normal function from nonsense-mutated genes, and small molecules such as aminoglycosides and PTC124 have exhibited promising results for treating patients with cystic fibrosis and Duchenne muscular dystrophy. Transgenic expression of suppressor-tRNAs and depleting translation termination factors are, among others, potential strategies for treating PTC-associated diseases. In this review, the potential of using readthrough strategies as a therapy for cancer syndromes is discussed, and we consider the effect of nonsense-mediated decay and other factors on readthrough efficiency. © 2012 Elsevier Ltd.
Keywords: Aminoglycosides; Hereditary cancer syndromes; Nonsense-mediated decay (NMD); Nonsense-suppression; Premature termination codon (PTC); PTC124; Readthrough; Suppressor-tRNA

Cell-based in vitro models for predicting drug permeability - Sarmento, B.; Andrade, F.; Da Silva, S.B.; Rodrigues, F.; Das Neves, J.; Ferreira, D. (Expert Opinion on Drug Metabolism and ToxicologyExpert Opin. Drug Metab. Toxicol., 2012)
In vitro cell models have been used to predict drug permeation in early stages of drug development, since they represent an easy and reproducible method, allowing the tracking of drug absorption rate and mechanism, with an advantageous costbenefit ratio. Such cell-based models are mainly composed of immortalized cells with an intrinsic ability to grow in a monolayer when seeded in permeable supports, maintaining their physiologic characteristics regarding epithelium cell physiology and functionality. Areas covered: This review summarizes the most important intestinal, pulmonary, nasal, vaginal, rectal, ocular and skin cell-based in vitro models for predicting the permeability of drugs. Moreover, the similitude between in vitro cell models and in vivo conditions are discussed, providing evidence that each model may provisionally resemble different drug absorption route. Expert opinion: Despite the widespread use of in vitro cell models for drug permeability and absorption evaluation purposes, a detailed study on the properties of these models and their in vitroin vivo correlation compared with human data are required to further use in order to consider a future drug discovery optimization and clinical development. © 2012 Informa UK, Ltd.
Keywords: Animals; Caco-2 Cells; carcinoma cell; cell differentiation; cell growth; Cell Line; Cell Membrane Permeability; cell models; cell proliferation; cell strain CACO 2; cell type; Cells; conjunctiva; drug absorption; drug bioavailability; drug delivery system; drug penetration; drug screening; drug transport; epithelium cell; Eye; human; Humans; in vitro models; in vitro study; in vitroin vivo correlation; Intestinal Absorption; intestinal mucosa; intestine cell; Intestines; Lung; lung alveolus cell; Models, Biological; molecular weight; nasal cell; nonhuman; ocular cell; permeability; Pharmaceutical Preparations; rectal cell; review; Skin; skin cell; vaginal cell

Chitosan drives anti-inflammatory macrophage polarisation and pro-inflammatory dendritic cell stimulation. - Oliveira, M.I.; Santos, S.G.; Oliveira, M.J.; Torres, A.L.; Barbosa, M.A. (European cells & materialsEur Cell Mater, 2012)
Macrophages and dendritic cells (DC) share the same precursor and play key roles in immunity. Modulation of their behaviour to achieve an optimal host response towards an implanted device is still a challenge. Here we compare the differentiation process and polarisation of these related cell populations and show that they exhibit different responses to chitosan (Ch), with human monocyte-derived macrophages polarising towards an anti-inflammatory phenotype while their DC counterparts display pro-inflammatory features. Macrophages and DC, whose interactions with biomaterials are frequently analysed using fully differentiated cells, were cultured directly on Ch films, rather than exposed to the polymer after complete differentiation. Ch was the sole stimulating factor and activated both macrophages and DC, without leading to significant T cell proliferation. After 10 d on Ch, macrophages significantly down-regulated expression of pro-inflammatory markers, CD86 and MHCII. Production of pro-inflammatory cytokines, particularly TNF-α, decreased with time for cells cultured on Ch, while anti-inflammatory IL-10 and TGF-β1, significantly increased. Altogether, these results suggest an M2c polarisation. Also, macrophage matrix metalloproteinase activity was augmented and cell motility was stimulated by Ch. Conversely, DC significantly enhanced CD86 expression, reduced IL-10 secretion and increased TNF-α and IL-1β levels. Our findings indicate that cells with a common precursor may display different responses, when challenged by the same biomaterial. Moreover, they help to further comprehend macrophage/DC interactions with Ch and the balance between pro- and anti-inflammatory signals associated with implant biomaterials. We propose that an overall pro-inflammatory reaction may hide the expression of anti-inflammatory cytokines, likely relevant for tissue repair/regeneration.
Keywords: antibody specificity; Antigens, CD86; article; Biocompatible Materials; biomaterial; biosynthesis; CD86 antigen; Cell culture; cell differentiation; cell motion; Cell Movement; Cells, Cultured; chitosan; cytology; dendritic cell; Dendritic Cells; drug effect; flow cytometry; Histocompatibility Antigens Class II; HLA antigen class 2; human; Humans; IL10 protein, human; immunology; interleukin 10; Interleukin-10; macrophage; Macrophages; metabolism; monocyte; Monocytes; Organ Specificity; transforming growth factor beta1; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

Tissue Engineering and Regenerative Medicine - Nascimento D, Silva A, Oliveira MJ Barbosa MA Pinto-do-Ó P. (Tissue Engineering and Regenerative Medicine, 2012)

Dissection and reconstruction of the extracellular matrix - a cardiac regenerative niche - Nascimento D.; Silva A.; Oliveira MJ.; Barbosa MA.; Pinto-do-Ó P. (Journal of Tissue Engineering and Regenerative Medicine, 2012)
Cited By (since 1996):1Export Date: 2 October 2013Source: Scopus

E-cadherin dysfunction in gastric cancer - Cellular consequences, clinical applications and open questions - Carneiro, P.; Fernandes, M.S.; Figueiredo, J.; Caldeira, J.; Carvalho, J.; Pinheiro, H.; Leite, M.; Melo, S.; Oliveira, P.; Simões-Correia, J.; Oliveira, M.J.; Carneiro, F.; et al. (FEBS LettersFEBS Lett., 2012)
E-cadherin plays a major role in cell-cell adhesion and inactivating germline mutations in its encoding gene predispose to hereditary diffuse gastric cancer. Evidence indicates that aside from its recognized role in early tumourigenesis, E-cadherin is also pivotal for tumour progression, including invasion and metastization. Herein, we discuss E-cadherin alterations found in a cancer context, associated cellular effects and signalling pathways, and we raise new key questions that will impact in the management of GC patients and families. © 2012 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
Keywords: Adhesion; Cadherins; cancer growth; cancer invasion; cancer patient; cancer susceptibility; cell adhesion; complex formation; conference paper; E-cadherin; embryo development; endocytosis; epigenetics; epithelial mesenchymal transition; Gastric cancer; gene mutation; gene silencing; genetic susceptibility; Germ-Line Mutation; HDGC; Helicobacter infection; Helicobacter Infections; Helicobacter pylori; histone deacetylase inhibitor; human; Humans; Invasion; metastasis; molecular pathology; nonhuman; priority journal; protein analysis; protein depletion; protein expression; protein function; protein structure; regulatory mechanism; signal transduction; Signalling; stomach cancer; stomach carcinogenesis; Stomach Neoplasms; Tumour; uvomorulin

The effect of adsorbed fibronectin and osteopontin on macrophage adhesion and morphology on hydrophilic and hydrophobic model surfaces - Maciel, J.; Oliveira, M.I.; Gonalves, R.M.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2012)
Macrophages play a crucial role in the host response to biomaterials. Here we investigated the effect of adsorbed fibronectin (FN) and osteopontin (OPN), two important proteins for tissue repair, on macrophage adhesion and morphology. Since cell-biomaterial interactions are modulated via proteins adsorbed onto biomaterial surfaces, FN and OPN were adsorbed on model self-assembled monolayers (SAMs) of alkanethiols on gold with different functional terminal groups (CH 3, OH and tetra(ethylene-glycol)). The initial interaction of inflammatory cells with a biomaterial is crucial for the ensuing phases of an inflammatory reaction. For this reason short-term cultures of primary human macrophages were performed. To account for the competitive adsorption of other proteins serum was added to the culture medium and the effect compared with serum-free medium cultures. In the presence of serum hydrophilic surfaces increased macrophage adhesion. In particular, FN induced a higher cell density, while OPN tended to decrease it. In serum-free medium cell adhesion was greater on hydrophobic surfaces, except for OPN-coated SAMs. Importantly, FN no longer enhanced macrophage adhesion, while OPN maintained its inhibitory effect. Cell polarization studies indicated that macrophage morphology variations induced by surface chemistry are overcome by pre-adsorbed OPN. Taken together our results show that in the presence of serum macrophage adhesion is promoted by FN hydrophilic surfaces, but impaired on OPN-coated surfaces. The effects of inhibited macrophage adhesion on macrophage fusion, and its relevance to the initial stages of the inflammatory response to biomaterials are discussed. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: alkane; article; biomaterial; Biomaterials; cell adhesion; cell density; cell interaction; cell structure; controlled study; culture medium; cytoskeleton; Fibronectin; functional group; gold; human; human cell; hydrophilicity; hydrophobicity; inflammatory cell; macrophage; Macrophages; nanomaterial; Osteopontin; priority journal; self assembled monolayer; Self-assembled monolayers; Tetra; thiol; tissue repair

Effect of gastric environment on Helicobacter pylori adhesion to a mucoadhesive polymer - Nogueira, F.; Gonçalves, I.C.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2012)
Helicobacter pylori infection has been associated with several gastric diseases. This bacterium colonizes the gastric mucosa of half of the world's population, and available treatments are unsuccessful in practically one in every five patients. Mucoadhesive polymers, such as chitosan, are being investigated as gastric drug delivery systems. However, since chitosan is also known for its antimicrobial properties, this work aims to evaluate H. pylori interactions with chitosan under simulated gastric environments, namely using various pHs (2.6, 4 and 6), pepsin and urea. To enable the visualization of adherent bacteria, ultrathin chitosan films were produced by spin-coating on gold/glass surfaces, cross-linked with genipin and characterized by Fourier transform infrared reflection absorption spectroscopy, ellipsometry and electrokinetic analysis. Films with homogeneous thickness of 11.7 ± 0.6 nm were produced, and were stable and protonated at all the pHs used. Furthermore, they adsorbed pepsin in all these pHs, in contrast to urea, of which a small adsorption was only observed at pH 6. H. pylori binding to chitosan was higher at pH 2.6 although most of adherent bacteria were dead. The presence of pepsin decreased bacterial adhesion, but increased its viability while in a more stressed morphology (coccoid form). The presence of urea did not affect the amount, morphology or viability of chitosan-adherent bacteria. In suspension, the decrease in pH changed H. pylori zeta potential from negative to positive. Moreover, bacteria were only culturable when incubated in pH 6 with and without urea (without pepsin). This work demonstrates that chitosan has the capacity to bind and kill H. pylori in a range of pHs independently of urea. This opens new perspectives for the application of chitosan-based materials to the elimination of H. pylori gastric colonization, though pepsin might appear to be an obstacle. © 2012 Acta Materialia Inc.
Keywords: Bacterial adhesion; Biomaterials; chitosan; Helicobacter pylori; Thin films

The effect of octadecyl chain immobilization on the hemocompatibility of poly (2-hydroxyethyl methacrylate) - Fischer, M.; Baptista, C.P.; Gonçalves, I.C.; Ratner, B.D.; Sperling, C.; Werner, C.; Martins, C.L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2012)
Albumin-scavenging surfaces decorated with n-alkyl chains represent an established strategy for blood-contacting applications. To evaluate this concept, a set of poly (2-hydroxyethyl methacrylate) (pHEMA) films modified with different amounts of octadecyl isocyanate (C18) was investigated in an in vitro hemocompatibility assay using freshly drawn human whole blood. In addition, the hydrogel materials were thoroughly characterized with respect to changes in wettability and elasticity, which accompanied the gradual chemical modification of pHEMA. An increase of the surface C18 content induced enhanced hydrophobicity and stiffness. Immobilization of C18 chains was found to substantially reduce the coagulation activation and the complement activation by the pHEMA films. Platelet adhesion and degranulation (PF4 release) were similar on the modified and the unmodified pHEMA. Platelet adhesion to pHEMA hydrogels was lower than the polytetrafluoroethylene reference. We conclude that the immobilization of octadecyl chains improved the hemocompatibility of pHEMA materials under conditions that might be encountered in low shear blood flow. © 2012 Elsevier Ltd.
Keywords: Adhesion; Albumin; article; Biological materials; Biomaterials; Blood; Blood flow; Chemical modification; Coagulation; controlled study; Degranulation; Elasticity; Haemocompatibility; Hemocompatibility; human; hydrogel; in vitro study; In-vitro; isocyanate; Octadecyl; octadecyl isocyanate; PHEMA; Platelet adhesion; Platelets; Poly(2-hydroxyethyl methacrylate); PolyHEMA; polymacon; priority journal; Protein adsorption; thrombocyte adhesion; unclassified drug; wettability; Whole blood

Endothelialization of chitosan porous conduits via immobilization of a recombinant fibronectin fragment (rhFNIII 7-10) - Amaral, I.F.; Neiva, I.; Ferreira da Silva, F.; Sousa, S.R.; Piloto, A.M.; Lopes, C.D.F.; Barbosa, M.A.; Kirkpatrick, C.J.; Pêgo, A.P. (Acta BiomaterialiaActa Biomater., 2012)
The present study aimed to develop a pre-endothelialized chitosan (CH) porous hollowed scaffold for application in spinal cord regenerative therapies. CH conduits with different degrees of acetylation (DA; 4% and 15%) were prepared, characterized (microstructure, porosity and water uptake) and functionalized with a recombinant fragment of human fibronectin (rhFNIII 7-10). Immobilized rhFNIII 7-10 was characterized in terms of amount ( 125I-radiolabelling), exposure of cell-binding domains (immunofluorescence) and ability to mediate endothelial cell (EC) adhesion and cytoskeletal rearrangement. Functionalized conduits revealed a linear increase in immobilized rhFNIII 7-10 with rhFNIII 7-10 concentration, and, for the same concentration, higher amounts of rhFNIII 7-10 on DA 4% compared with DA 15%. Moreover, rhFNIII 7-10 concentrations as low as 5 and 20 μg ml
Keywords: Protein conformation; Protein radiolabelling; Spinal cord injury; Surface grafting; Three-dimensional scaffolds

Enhanced mesenchymal stromal cell recruitment via natural killer cells by incorporation of inflammatory signals in biomaterials - Almeida, C.R.; Vasconcelos, D.P.; Gonçalves, R.M.; Barbosa, M.A. (Journal of the Royal Society InterfaceJ. R. Soc. Interface, 2012)
An exacerbated inflammatory response questions biomaterial biocompatibility, but on the other hand, inflammation has a central role in the regulation of tissue regeneration. Therefore, it may be argued that an 'ideal' inflammatory response is crucial to achieve efficient tissue repair/regeneration. Natural killer (NK) cells, being one of the first populations arriving at an injury site, can have an important role in regulating bone repair/regeneration, particularly through interactions with mesenchymal stem/stromal cells (MSCs). Here, we studied how biomaterials designed to incorporate inflammatory signals affected NK cell behaviour and NK cell-MSC interactions. Adsorption of the pro-inflammatory molecule fibrinogen (Fg) to chitosan films led to a 1.5-fold increase in adhesion of peripheral blood human NK cells, without an increase in cytokine secretion. Most importantly, it was found that NK cells are capable of stimulating a threefold increase in human bone marrow MSC invasion, a key event taking place in tissue repair, but did not affect the expression of the differentiation marker alkaline phosphatase (ALP). Of significant importance, this NK cell-mediated MSC recruitment was modulated by Fg adsorption. Designing novel biomaterials leading to rational modulation of the inflammatory response is proposed as an alternative to current bone regeneration strategies. © 2011 The Royal Society.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1098/rsif.2011.0357Language of Original Document: EnglishCorrespondence Address: Almeida, C.R.; INEB-Instituto de Engenharia Biomédica, Biomaterials Division, NEWTherapies Group, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cralmeid@ineb.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; chitosan, 9012-76-4; fibrinogen, 9001-32-5; gamma interferon, 82115-62-6References: Mountziaris, P.M., Mikos, A.G., Modulation of the inflammatory response for enhanced bone tissue regeneration (2008) Tissue Eng. Part B Rev., 14, pp. 179-186. , doi:10. 1089/ten.teb.2008.0038;Anderson, J.M., Rodriguez, A., Chang, D.T., Foreign body reaction to biomaterials (2008) Semin. Immunol., 20, pp. 86-100. , doi:10.1016/j.smim.2007.11.004; Agaiby, A.D., Dyson, M., Immuno-inflammatory cell dynamics during cutaneous wound healing (1999) J. Anat., 195, pp. 531-542. , doi:10.1046/j.1469-7580.1999.19540531.x; Vivier, E., Tomasello, E., Baratin, M., Walzer, T., Ugolini, S., Functions of natural killer cells (2008) Nat. Immunol., 9, pp. 503-510. , doi:10.1038/ni1582; Aggarwal, S., Pittenger, M.F., Human mesenchymal stem cells modulate allogeneic immune cell responses (2005) Blood, 105, pp. 1815-1822. , doi:10.1182/blood- 2004-04-1559; Caplan, A.I., Adult mesenchymal stem cells for tissue engineering versus regenerative medicine (2007) J. Cell. Physiol., 213, pp. 341-347. , doi:10.1002/jcp.21200; Pittenger, M.F., Multilineage potential of adult human mesenchymal stem cells (1999) Science, 284, pp. 143-147. , doi:10.1126/science.284.5411.143; Poggi, A., Prevosto, C., Massaro, A.M., Negrini, S., Urbani, S., Pierri, I., Saccardi, R., Zocchi, M.R., Interaction between human NK cells and bone marrow stromal cells induces NK cell triggering: Role of NKp30 and NKG2D receptors (2005) J. Immunol., 175, pp. 6352-6360. , doi:10.175/10/6352[pii]; Rasmusson, I., Ringden, O., Sundberg, B., Le Blanc, K., Mesenchymal stem cells inhibit the formation of cytotoxic T lymphocytes, but not activated cytotoxic T lymphocytes or natural killer cells (2003) Transplantation, 76, pp. 1208-1213. , doi:10.1097/01.TP.0000082540.43730.80; Götherström, C., Lundqvist, A., Duprez, I.R., Childs, R., Berg, L., Le Blanc, K., Fetal and adult multipotent mesenchymal stromal cells are killed by different pathways (2010) Cytotherapy, 13, pp. 269-278. , doi:10.3109/14653249.2010.523077; Jewett, A., Arasteh, A., Tseng, H.C., Behel, A., Arasteh, H., Yang, W., Cacalano, N.A., Paranjpe, A., Strategies to rescue mesenchymal stem cells (MSCs) and dental pulp stem cells (DPSCs) from NK cell mediated cytotoxicity (2010) PLoS ONE, 5, pp. e9874. , doi:10.1371/journal.pone. 0009874; Sotiropoulou, P.A., Perez, S.A., Gritzapis, A.D., Baxevanis, C.N., Papamichail, M., Interactions between human mesenchymal stem cells and natural killer cells (2006) Stem Cells, 24, pp. 74-85. , doi:10.1634/stemcells.2004-0359; Spaggiari, G.M., Capobianco, A., Becchetti, S., Mingari, M.C., Moretta, L., Mesenchymal stem cell-natural killer cell interactions: Evidence that activated NK cells are capable of killing MSCs, whereas MSCs can inhibit IL-2- Induced NK-cell proliferation (2006) Blood, 107, pp. 1484-1490. , doi:10.1182/blood-2005-07-2775; Tseng, H.C., Increased lysis of stem cells but not their differentiated cells by natural killer cells; dedifferentiation or reprogramming activates NK cells (2010) PLoS ONE, 5, pp. e11590. , doi:10.1371/journal.pone.0011590; Krampera, M., Role for interferon-gamma in the immunomodulatory activity of human bone marrow mesenchymal stem cells (2006) Stem Cells, 24, pp. 386-398. , doi:10.1634/stemcells.2005-0008; Pradier, A., Passweg, J., Villard, J., Kindler, V., Human bone marrow stromal cells and skin fibroblasts inhibit natural killer cell proliferation and cytotoxic activity (2010) Cell Transplant., , doi:10.3727/096368910X 536545; Selmani, Z., Human leukocyte antigen-G5 secretion by human mesenchymal stem cells is required to suppress T lymphocyte and natural killer function and to induce CD4+CD25highFOXP3+ regulatory T cells (2008) Stem Cells, 26, pp. 212-222. , doi:10.1634/stemcells. 2007-0554; Spaggiari, G.M., Capobianco, A., Abdelrazik, H., Becchetti, F., Mingari, M.C., Moretta, L., Mesenchymal stem cells inhibit natural killer-cell proliferation, cytotoxicity, and cytokine production: Role of indoleamine 2,3-dioxygenase and prostaglandin E2 (2008) Blood, 111, pp. 1327-1333. , doi:10.1182/blood-2007-02- 074997; Salem, H.K., Thiemermann, C., Mesenchymal stromal cells: Current understanding and clinical status (2010) Stem Cells, 28, pp. 585-596. , doi:10.1002/stem.269; Dimitriou, R., Tsiridis, E., Giannoudis, P.V., Current concepts of molecular aspects of bone healing (2005) Injury, 36, pp. 1392-1404. , doi:10.1016/j.injury.2005.07.019; Rifas, L., T-cell cytokine induction of BMP-2 regulates human mesenchymal stromal cell differentiation and mineralization (2006) J. Cell. Biochem., 98, pp. 706-714. , doi:10.1002/jcb.20933; Rifas, L., Arackal, S., Weitzmann, M.N., Inflammatory T cells rapidly induce differentiation of human bone marrow stromal cells into mature osteoblasts (2003) J. Cell. Biochem., 88, pp. 650-659. , doi:10.1002/jcb.10436; Champagne, C.M., Takebe, J., Offenbacher, S., Cooper, L.F., Macrophage cell lines produce osteoinductive signals that include bone morphogenetic protein-2 (2002) Bone, 30, pp. 26-31. , doi:10.1016/S8756-3282(01)00638-X; Gerstenfeld, L.C., Cho, T.J., Kon, T., Aizawa, T., Cruceta, J., Graves, B.D., Einhorn, T.A., Impaired intramembranous bone formation during bone repair in the absence of tumor necrosis factor-alpha signaling (2001) Cells Tissues Organs, 169, pp. 285-294. , doi:10.1159/ 000047893; Gerstenfeld, L.C., Cho, T.J., Kon, T., Aizawa, T., Tsay, A., Fitch, J., Barnes, G.L., Einhorn, T.A., Impaired fracture healing in the absence of TNF-alpha signaling: The role of TNF-α in endochondral cartilage resorption (2003) J. Bone Miner. Res., 18, pp. 1584-1592. , doi:10.1359/jbmr.2003.18.9.1584; Duque, G., Huang, D.C., Macoritto, M., Rivas, D., Yang, X.F., Ste-Marie, L.G., Kremer, R., Autocrine regulation of interferon gamma in mesenchymal stem cells plays a role in early osteoblastogenesis (2009) Stem Cells, 27, pp. 550-558. , doi:10.1634/stemcells.2008-0886; Honczarenko, M., Le, Y., Swierkowski, M., Ghiran, I., Glodek, A.M., Silberstein, L.E., Human bone marrow stromal cells express a distinct set of biologically functional chemokine receptors (2006) Stem Cells, 24, pp. 1030-1041. , doi:10.1634/stemcells.2005-0319; Robertson, M.J., Role of chemokines in the biology of natural killer cells (2002) J. Leukoc Biol., 71, pp. 173-183; Rodrigues, S.N., Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367. , doi:10.1016/j.biomaterials.2006.06.010; Peled, E., Boss, J., Bejar, J., Zinman, C., Seliktar, D., A novel poly(ethylene glycol)-fibrinogen hydrogel for tibial segmental defect repair in a rat model (2007) J. Biomed. Mater. Res., 80, pp. 874-884. , doi:10.1002/jbm. a.30928; Bryceson, Y.T., March, M.E., Ljunggren, H.G., Long, E.O., Activation, coactivation, and costimulation of resting human natural killer cells (2006) Immunol. Rev., 214, pp. 73-91. , doi:10.1111/j.1600-065X.2006.00457.x; Muto, S., Vetvicka, V., Ross, G.D., CR3 (CD11b/ CD18) expressed by cytotoxic T cells and natural killer cells is upregulated in a manner similar to neutrophil CR3 following stimulation with various activating agents (1993) J. Clin. Immunol., 13, pp. 175-184. , doi:10.1007/ BF00919970; Ross, G.D., Vetvicka, V., CR3 (CD11b, CD18): A phagocyte and NK cell membrane receptor with multiple ligand specificities and functions (1993) Clin. Exp. Immunol., 92, pp. 181-184. , doi:10.1111/j.1365-2249.1993.tb03377.x; Lishko, V.K., Kudryk, B., Yakubenko, V.P., Yee, V.C., Ugarova, T.P., Regulated unmasking of the cryptic binding site for integrin alpha M beta 2 in the gamma C-domain of fibrinogen (2002) Biochemistry, 41, pp. 12942-12951. , doi:10.1021/bi026324c; Mwale, F., Iordanova, M., Demers, C.N., Steffen, T., Roughley, P., Antoniou, J., Biological evaluation of chitosan salts cross-linked to genipin as a cell scaffold for disk tissue engineering (2005) Tissue Eng., 11, pp. 130-140. , doi:10.1089/ten.2005.11.130; Prabaharan, M., Jayakumar, R., Chitosan-graft-beta-cyclodextrin scaffolds with controlled drug release capability for tissue engineering applications (2009) Int. J. Biol. Macromol., 44, pp. 320-325. , doi:10.1016/j.ijbiomac.2009.01.005; Agnihotri, S.A., Mallikarjuna, N.N., Aminabhavi, T.M., Recent advances on chitosan-based micro-and nanoparticles in drug delivery (2004) J. Control Release, 100, pp. 5-28. , doi:10.1016/j.jconrel.2004.08.010; Barbosa, M.A., Granja, P.L., Barrias, C.C., Amaral, I.F., Polysaccharides as scaffolds for bone regeneration (2005) ITBM-RBM, 26, pp. 212-217. , doi:10.1016/j.rbmret.2005.04.006; Berger, J., Reist, M., Mayer, J.M., Felt, O., Gurny, R., Structure and interactions in chitosan hydrogels formed by complexation or aggregation for biomedical applications (2004) Eur. J. Pharm. Biopharm., 57, pp. 35-52. , doi:10.1016/S0939-6411(03)00160-7; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) J. Biomater. Sci. Polym. Ed., 18, pp. 469-485. , doi:10.1163/ 156856207780425068; Barbosa, J.N., Amaral, I.F., Aguas, A.P., Barbosa, M.A., Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds (2010) J. Biomed. Mater. Res., 93 A, pp. 20-28. , doi:10.1002/jbm.a.32499; Oliveira, S.M., Mijares, D.Q., Turner, G., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: In vivo studies (2009) Tissue Eng. Part A, 15, pp. 635-643. , doi:10.1089/ten.tea.2008.0052; Amaral, I.F., Sampaio, P., Barbosa, M.A., Three-dimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2006) J. Biomed. Mater. Res., 76, pp. 335-346. , doi:10.1002/jbm.a.30522; Goncalves, R.M., Martins, M.C., Almeida-Porada, G., Barbosa, M.A., Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers (2009) Biomaterials, 30, pp. 6879-6887. , doi:10.1016/j.biomaterials.2009.09.010; Dominici, M., Minimal criteria for defining multipotent mesenchymal stromal cells. The International Society for Cellular Therapy position statement (2006) Cytotherapy, 8, pp. 315-317. , doi:10.1080/14653240600855905; Siddappa, R., Licht, R., Van Blitterswijk, C., De Boer, J., Donor variation and loss of multipotency during in vitro expansion of human mesenchymal stem cells for bone tissue engineering (2007) J. Orthop. Res., 25, pp. 1029-1041. , doi:10.1002/jor.20402; Maeda, Y., Kimura, Y., Antitumor Effects of Various Low-Molecular-Weight Chitosans Are Due to Increased Natural Killer Activity of Intestinal Intraepithelial Lymphocytes in Sarcoma 180-Bearing Mice (2004) Journal of Nutrition, 134 (4), pp. 945-950; Zaharoff, D.A., Rogers, C.J., Hance, K.W., Schlom, J., Greiner, J.W., Chitosan solution enhances both humoral and cell-mediated immune responses to subcutaneous vaccination (2007) Vaccine, 25, pp. 2085-2094. , doi:10. 1016/j.vaccine.2006.11.034; Tang, L., Eaton, J.W., Fibrin(ogen) mediates acute inflammatory responses to biomaterials (1993) J. Exp. Med., 178, pp. 2147-2156. , doi:10.1084/jem.178.6.2147; Drew, A.F., Liu, H., Davidson, J.M., Daugherty, C.C., Degen, J.L., Wound-healing defects in mice lacking fibrinogen (2001) Blood, 97, pp. 3691-3698. , doi:10.1182/blood. V97.12.3691; Flick, M.J., Du, X., Degen, J.L., Fibrin(ogen)- alpha M beta 2 interactions regulate leukocyte function and innate immunity in vivo (2004) Exp. Biol. Med. (Maywood), 229, pp. 1105-1110. , doi:10.229/11/1105[pii]; Culley, F.J., Natural killer cell signal integration balances synapse symmetry and migration (2009) PLoS Biol., 7, pp. e1000159. , doi:10.1371/journal.pbio.1000159; Dustin, M.L., Cell adhesion molecules and actin cytoskeleton at immune synapses and kinapses (2007) Curr. Opin. Cell Biol., 19, pp. 529-533. , doi:10.1016/j.ceb.2007.08.003; Jacobs, R., Hintzen, G., Kemper, A., Beul, K., Kempf, S., Behrens, G., Sykora, K.W., Schmidt, R.E., CD56bright cells differ in their KIR repertoire and cytotoxic features from CD56dim NK cells (2001) Eur. J. Immunol., 31, pp. 3121-3127. , doi:10.1002/1521-4141(2001010)31: 10〈3121::AID-IMMU3121〉3.0. CO;2-4; Anfossi, N., Human NK cell education by inhibitory receptors for MHC class I (2006) Immunity, 25, pp. 331-342. , doi:10.1016/j.immuni.2006.06.013; Nolte-'t Hoen, E.N.M., Almeida, C.R., Cohen, N.R., Nedvetzki, S., Yarwood, H., Davis, D.M., Increased surveillance of cells in mitosis by human NK cells suggests a novel strategy for limiting tumor growth and viral replication (2006) Blood, 109, pp. 670-673. , doi:10.1182/blood-2006-07- 036509; Hemeda, H., Jakob, M., Ludwig, A.K., Giebel, B., Lang, S., Brandau, S., Interferon-gamma and tumor necrosis factor-alpha differentially affect cytokine expression and migration properties of mesenchymal stem cells (2010) Stem Cells Dev., 19, pp. 693-706; Liippo, J., Toriseva, M., Kähäri, V.-M., Natural killer cell in wound healing (2009) Natural Killer Cells - Basic Science and Clinical Application, pp. 519-525. , eds M. Lotze & A. Thomson, New York, NY: Academic Press; Soderstrom, K., Stein, E., Colmenero, P., Purath, U., Muller-Ladner, U., De Matos, C.T., Tarner, I.H., Engleman, E.G., Natural killer cells trigger osteoclastogenesis and bone destruction in arthritis (2010) Proc. Natl Acad. Sci. USA, 107, pp. 13028-13033. , doi:10.1073/pnas.1000546107
Keywords: Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; biomaterial; Biomaterials; blood cell; Bone; bone marrow cell; Bone Regeneration; Bone repair; cell adhesion; Cell culture; cell differentiation; cell function; cell interaction; cell invasion; Cells; chitosan; Chitosan film; cytokine; Cytokine secretions; Differentiation markers; fibrinogen; gamma interferon; human; Human bone marrow; human cell; Inflammation; Inflammatory response; Mesenchymal Stem Cells; mesenchymal stroma cell; Mesenchymal stromal cells; natural killer cell; Natural killer cells; NK cells; ossification; Pathology; Peripheral blood; Phosphatases; protein expression; Tissue; Tissue regeneration; tissue repair

Epithelial E- and P-cadherins: Role and clinical significance in cancer - Paredes, J.; Figueiredo, J.; Albergaria, A.; Oliveira, P.; Carvalho, J.; Ribeiro, A.S.; Caldeira, J.; Costa, A.M.; Simões-Correia, J.; Oliveira, M.J.; Pinheiro, H.; Pinho, S.S.; et al. (Biochimica et Biophysica Acta - Reviews on CancerBiochim. Biophys. Acta Rev. Cancer, 2012)
E-cadherin and P-cadherin are major contributors to cell-cell adhesion in epithelial tissues, playing pivotal roles in important morphogenetic and differentiation processes during development, and in maintaining integrity and homeostasis in adult tissues. It is now generally accepted that alterations in these two molecules are observed during tumour progression of most carcinomas. Genetic or epigenetic alterations in E- and P-cadherin-encoding genes (CDH1 and CDH3, respectively), or alterations in their proteins expression, often result in tissue disorder, cellular de-differentiation, increased invasiveness of tumour cells and ultimately in metastasis. In this review, we will discuss the major properties of E- and P-cadherin molecules, its regulation in normal tissue, and their alterations and role in cancer, with a specific focus on gastric and breast cancer models. © 2012 Elsevier B.V.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BBACEdoi: 10.1016/j.bbcan.2012.05.002Language of Original Document: EnglishCorrespondence Address: Seruca, R.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3Tradenames: pf 03732010References: Cavallaro, U., Christofori, G., Cell adhesion and signalling by cadherins and Ig-CAMs in cancer (2004) Nat. Rev. Cancer, 4, pp. 118-132;Gerrow, K., El-Husseini, A., Cell adhesion molecules at the synapse (2006) Front. Biosci., 11, pp. 2400-2419; Nollet, F., Kools, P., van Roy, F., Phylogenetic analysis of the cadherin superfamily allows identification of six major subfamilies besides several solitary members (2000) J. Mol. Biol., 299, pp. 551-572; Takeichi, M., Cadherins in cancer: implications for invasion and metastasis (1993) Curr. Opin. Cell Biol., 5, pp. 806-811; Pignatelli, M., Bodmer, W.F., Genetics and biochemistry of collagen binding-triggered glandular differentiation in a human colon carcinoma cell line (1988) Proc. Natl. Acad. Sci. U. S. A., 85, pp. 5561-5565; Takeichi, M., Morphogenetic roles of classic cadherins (1995) Curr. Opin. Cell Biol., 7, pp. 619-627; Shapiro, L., Fannon, A.M., Kwong, P.D., Thompson, A., Lehmann, M.S., Grubel, G., Legrand, J.F., Hendrickson, W.A., Structural basis of cell-cell adhesion by cadherins (1995) Nature, 374, pp. 327-337; Ozawa, M., Ringwald, M., Kemler, R., Uvomorulin-catenin complex formation is regulated by a specific domain in the cytoplasmic region of the cell adhesion molecule (1990) Proc. Natl. Acad. Sci. U. S. A., 87, pp. 4246-4250; Blaschuk, O.W., Sullivan, R., David, S., Pouliot, Y., Identification of a cadherin cell adhesion recognition sequence (1990) Dev. Biol., 139, pp. 227-229; Ozawa, M., Baribault, H., Kemler, R., The cytoplasmic domain of the cell adhesion molecule uvomorulin associates with three independent proteins structurally related in different species (1989) EMBO J., 8, pp. 1711-1717; Gumbiner, B.M., McCrea, P.D., Catenins as mediators of the cytoplasmic functions of cadherins (1993) J. Cell Sci. Suppl., 17, pp. 155-158; Yap, A.S., Niessen, C.M., Gumbiner, B.M., The juxtamembrane region of the cadherin cytoplasmic tail supports lateral clustering, adhesive strengthening, and interaction with p120ctn (1998) J. Cell Biol., 141, pp. 779-789; Van Aken, E., De Wever, O., Correia da Rocha, A.S., Mareel, M., Defective E-cadherin/catenin complexes in human cancer (2001) Virchows Arch., 439, pp. 725-751; Mareel, M., Oliveira, M.J., Madani, I., Cancer invasion and metastasis: interacting ecosystems (2009) Virchows Arch., 454, pp. 599-622; Makrilia, N., Kollias, A., Manolopoulos, L., Syrigos, K., Cell adhesion molecules: role and clinical significance in cancer (2009) Cancer Invest., 27, pp. 1023-1037; Bussemakers, M.J., van Bokhoven, A., Voller, M., Smit, F.P., Schalken, J.A., The genes for the calcium-dependent cell adhesion molecules P- and E-cadherin are tandemly arranged in the human genome (1994) Biochem. Biophys. Res. Commun., 203, pp. 1291-1294; Berx, G., Staes, K., van Hengel, J., Molemans, F., Bussemakers, M.J., van Bokhoven, A., van Roy, F., Cloning and characterization of the human invasion suppressor gene E-cadherin (CDH1) (1995) Genomics, 26, pp. 281-289; Jarrard, D.F., Paul, R., van Bokhoven, A., Nguyen, S.H., Bova, G.S., Wheelock, M.J., Johnson, K.R., Isaacs, W.B., P-cadherin is a basal cell-specific epithelial marker that is not expressed in prostate cancer (1997) Clin. Cancer Res., 3, pp. 2121-2128; Hubbard, T.J., Aken, B.L., Ayling, S., Ballester, B., Beal, K., Bragin, E., Brent, S., Flicek, P., Ensembl 2009 (2009) Nucleic Acids Res., 37, pp. D690-D697; Faraldo, M.L., Cano, A., The 5' flanking sequences of the mouse P-cadherin gene. Homologies to 5' sequences of the E-cadherin gene and identification of a first 215 base-pair intron (1993) J. Mol. Biol., 231, pp. 935-941; van Roy, F., Berx, G., The cell-cell adhesion molecule E-cadherin (2008) Cell. Mol. Life Sci., 65, pp. 3756-3788; Stemmler, M.P., Cadherins in development and cancer (2008) Mol. Biosyst., 4, pp. 835-850; Paredes, J., Albergaria, A., Oliveira, J.T., Jeronimo, C., Milanezi, F., Schmitt, F.C., P-cadherin overexpression is an indicator of clinical outcome in invasive breast carcinomas and is associated with CDH3 promoter hypomethylation (2005) Clin. Cancer Res., 11, pp. 5869-5877; Sakharkar, K.R., Chow, V.T., PPD-proteome profile database (2004) In Silico Biol., 4, pp. 219-223; Thomas, D.J., Rosenbloom, K.R., Clawson, H., Hinrichs, A.S., Trumbower, H., Raney, B.J., Karolchik, D., Kent, W.J., The ENCODE Project at UC Santa Cruz (2007) Nucleic Acids Res., 35, pp. D663-D667; Oliveira, P., Sanges, R., Huntsman, D., Stupka, E., Oliveira, C., Characterization of the intronic portion of cadherin superfamily members, common cancer orchestrators (2012) Eur. J. Hum. Genet.; Hosono, S., Gross, I., English, M.A., Hajra, K.M., Fearon, E.R., Licht, J.D., E-cadherin is a WT1 target gene (2000) J. Biol. Chem., 275, pp. 10943-10953; Liu, Y.N., Lee, W.W., Wang, C.Y., Chao, T.H., Chen, Y., Chen, J.H., Regulatory mechanisms controlling human E-cadherin gene expression (2005) Oncogene, 24, pp. 8277-8290; Behrens, J., Lowrick, O., Klein-Hitpass, L., Birchmeier, W., The E-cadherin promoter: functional analysis of a G.C-rich region and an epithelial cell-specific palindromic regulatory element (1991) Proc. Natl. Acad. Sci. U. S. A., 88, pp. 11495-11499; Cano, A., Perez-Moreno, M.A., Rodrigo, I., Locascio, A., Blanco, M.J., del Barrio, M.G., Portillo, F., Nieto, M.A., The transcription factor snail controls epithelial-mesenchymal transitions by repressing E-cadherin expression (2000) Nat. Cell Biol., 2, pp. 76-83; Hajra, K.M., Chen, D.Y., Fearon, E.R., The SLUG zinc-finger protein represses E-cadherin in breast cancer (2002) Cancer Res., 62, pp. 1613-1618; Perez-Moreno, M.A., Locascio, A., Rodrigo, I., Dhondt, G., Portillo, F., Nieto, M.A., Cano, A., A new role for E12/E47 in the repression of E-cadherin expression and epithelial-mesenchymal transitions (2001) J. Biol. Chem., 276, pp. 27424-27431; Comijn, J., Berx, G., Vermassen, P., Verschueren, K., van Grunsven, L., Bruyneel, E., Mareel, M., van Roy, F., The two-handed E box binding zinc finger protein SIP1 downregulates E-cadherin and induces invasion (2001) Mol. Cell, 7, pp. 1267-1278; Eger, A., Aigner, K., Sonderegger, S., Dampier, B., Oehler, S., Schreiber, M., Berx, G., Foisner, R., DeltaEF1 is a transcriptional repressor of E-cadherin and regulates epithelial plasticity in breast cancer cells (2005) Oncogene, 24, pp. 2375-2385; Peinado, H., Olmeda, D., Cano, A., Snail, Zeb and bHLH factors in tumour progression: an alliance against the epithelial phenotype? (2007) Nat. Rev. Cancer, 7, pp. 415-428; Shi, Y., Sawada, J., Sui, G., Affar el, B., Whetstine, J.R., Lan, F., Ogawa, H., Nakatani, Y., Coordinated histone modifications mediated by a CtBP co-repressor complex (2003) Nature, 422, pp. 735-738; Jamora, C., DasGupta, R., Kocieniewski, P., Fuchs, E., Links between signal transduction, transcription and adhesion in epithelial bud development (2003) Nature, 422, pp. 317-322; Vandewalle, C., Comijn, J., De Craene, B., Vermassen, P., Bruyneel, E., Andersen, H., Tulchinsky, E., Berx, G., SIP1/ZEB2 induces EMT by repressing genes of different epithelial cell-cell junctions (2005) Nucleic Acids Res., 33, pp. 6566-6578; Aigner, K., Dampier, B., Descovich, L., Mikula, M., Sultan, A., Schreiber, M., Mikulits, W., Eger, A., The transcription factor ZEB1 (deltaEF1) promotes tumour cell dedifferentiation by repressing master regulators of epithelial polarity (2007) Oncogene, 26, pp. 6979-6988; Spaderna, S., Schmalhofer, O., Wahlbuhl, M., Dimmler, A., Bauer, K., Sultan, A., Hlubek, F., Brabletz, T., The transcriptional repressor ZEB1 promotes metastasis and loss of cell polarity in cancer (2008) Cancer Res., 68, pp. 537-544; Graff, J.R., Herman, J.G., Lapidus, R.G., Chopra, H., Xu, R., Jarrard, D.F., Isaacs, W.B., Baylin, S.B., E-cadherin expression is silenced by DNA hypermethylation in human breast and prostate carcinomas (1995) Cancer Res., 55, pp. 5195-5199; Shimomura, Y., Wajid, M., Shapiro, L., Christiano, A.M., P-cadherin is a p63 target gene with a crucial role in the developing human limb bud and hair follicle (2008) Development, 135, pp. 743-753; Carroll, D.K., Carroll, J.S., Leong, C.O., Cheng, F., Brown, M., Mills, A.A., Brugge, J.S., Ellisen, L.W., P63 regulates an adhesion programme and cell survival in epithelial cells (2006) Nat. Cell Biol., 8, pp. 551-561; Faraldo, M.M., Teuliere, J., Deugnier, M.A., Birchmeier, W., Huelsken, J., Thiery, J.P., Cano, A., Glukhova, M.A., Beta-catenin regulates P-cadherin expression in mammary basal epithelial cells (2007) FEBS Lett., 581, pp. 831-836; Le, T.L., Yap, A.S., Stow, J.L., Recycling of E-cadherin: a potential mechanism for regulating cadherin dynamics (1999) J. Cell Biol., 146, pp. 219-232; Bryant, D.M., Stow, J.L., The ins and outs of E-cadherin trafficking (2004) Trends Cell Biol., 14, pp. 427-434; Hinck, L., Nathke, I.S., Papkoff, J., Nelson, W.J., Dynamics of cadherin/catenin complex formation: novel protein interactions and pathways of complex assembly (1994) J. Cell Biol., 125, pp. 1327-1340; Chen, Y.T., Stewart, D.B., Nelson, W.J., Coupling assembly of the E-cadherin/beta-catenin complex to efficient endoplasmic reticulum exit and basal-lateral membrane targeting of E-cadherin in polarized MDCK cells (1999) J. Cell Biol., 144, pp. 687-699; Lock, J.G., Stow, J.L., Rab11 in recycling endosomes regulates the sorting and basolateral transport of E-cadherin (2005) Mol. Biol. Cell, 16, pp. 1744-1755; Bryant, D.M., Kerr, M.C., Hammond, L.A., Joseph, S.R., Mostov, K.E., Teasdale, R.D., Stow, J.L., EGF induces macropinocytosis and SNX1-modulated recycling of E-cadherin (2007) J. Cell Sci., 120, pp. 1818-1828; Ling, K., Bairstow, S.F., Carbonara, C., Turbin, D.A., Huntsman, D.G., Anderson, R.A., Type I gamma phosphatidylinositol phosphate kinase modulates adherens junction and E-cadherin trafficking via a direct interaction with mu 1B adaptin (2007) J. Cell Biol., 176, pp. 343-353; Mosesson, Y., Mills, G.B., Yarden, Y., Derailed endocytosis: an emerging feature of cancer (2008) Nat. Rev. Cancer, 8, pp. 835-850; Ireton, R.C., Davis, M.A., van Hengel, J., Mariner, D.J., Barnes, K., Thoreson, M.A., Anastasiadis, P.Z., Reynolds, A.B., A novel role for p120 catenin in E-cadherin function (2002) J. Cell Biol., 159, pp. 465-476; Davis, M.A., Ireton, R.C., Reynolds, A.B., A core function for p120-catenin in cadherin turnover (2003) J. Cell Biol., 163, pp. 525-534; Xiao, K., Garner, J., Buckley, K.M., Vincent, P.A., Chiasson, C.M., Dejana, E., Faundez, V., Kowalczyk, A.P., P120-Catenin regulates clathrin-dependent endocytosis of VE-cadherin (2005) Mol. Biol. Cell, 16, pp. 5141-5151; Taniuchi, K., Nakagawa, H., Hosokawa, M., Nakamura, T., Eguchi, H., Ohigashi, H., Ishikawa, O., Nakamura, Y., Overexpressed P-cadherin/CDH3 promotes motility of pancreatic cancer cells by interacting with p120ctn and activating rho-family GTPases (2005) Cancer Res., 65, pp. 3092-3099; Paredes, J., Stove, C., Stove, V., Milanezi, F., Van Marck, V., Derycke, L., Mareel, M., Schmitt, F., P-cadherin is up-regulated by the antiestrogen ICI 182,780 and promotes invasion of human breast cancer cells (2004) Cancer Res., 64, pp. 8309-8317; Palacios, F., Price, L., Schweitzer, J., Collard, J.G., D'Souza-Schorey, C., An essential role for ARF6-regulated membrane traffic in adherens junction turnover and epithelial cell migration (2001) EMBO J., 20, pp. 4973-4986; Figueiredo, J., Simoes-Correia, J., Soderberg, O., Suriano, G., Seruca, R., ADP-ribosylation factor 6 mediates E-cadherin recovery by chemical chaperones (2011) PLoS One, 6, pp. e23188; Palacios, F., Schweitzer, J.K., Boshans, R.L., D'Souza-Schorey, C., ARF6-GTP recruits Nm23-H1 to facilitate dynamin-mediated endocytosis during adherens junctions disassembly (2002) Nat. Cell Biol., 4, pp. 929-936; Otsuki, Y., Tanaka, M., Yoshii, S., Kawazoe, N., Nakaya, K., Sugimura, H., Tumor metastasis suppressor nm23H1 regulates Rac1 GTPase by interaction with Tiam1 (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 4385-4390; Morishige, M., Hashimoto, S., Ogawa, E., Toda, Y., Kotani, H., Hirose, M., Wei, S., Sabe, H., GEP100 links epidermal growth factor receptor signalling to Arf6 activation to induce breast cancer invasion (2008) Nat. Cell Biol., 10, pp. 85-92; Daniel, J.M., Reynolds, A.B., Tyrosine phosphorylation and cadherin/catenin function (1997) Bioessays, 19, pp. 883-891; Palacios, F., Tushir, J.S., Fujita, Y., D'Souza-Schorey, C., Lysosomal targeting of E-cadherin: a unique mechanism for the down-regulation of cell-cell adhesion during epithelial to mesenchymal transitions (2005) Mol. Cell. Biol., 25, pp. 389-402; Fujita, Y., Krause, G., Scheffner, M., Zechner, D., Leddy, H.E., Behrens, J., Sommer, T., Birchmeier, W., Hakai, a c-Cbl-like protein, ubiquitinates and induces endocytosis of the E-cadherin complex (2002) Nat. Cell Biol., 4, pp. 222-231; Pinho, S.S., Seruca, R., Gartner, F., Yamaguchi, Y., Gu, J., Taniguchi, N., Reis, C.A., Modulation of E-cadherin function and dysfunction by N-glycosylation (2011) Cell. Mol. Life Sci., 68, pp. 1011-1020; Zhu, W., Leber, B., Andrews, D.W., Cytoplasmic O-glycosylation prevents cell surface transport of E-cadherin during apoptosis (2001) EMBO J., 20, pp. 5999-6007; Zhou, F., Su, J., Fu, L., Yang, Y., Zhang, L., Wang, L., Zhao, H., Zha, X., Unglycosylation at Asn-633 made extracellular domain of E-cadherin folded incorrectly and arrested in endoplasmic reticulum, then sequentially degraded by ERAD (2008) Glycoconj. J., 25, pp. 727-740; Liwosz, A., Lei, T., Kukuruzinska, M.A., N-glycosylation affects the molecular organization and stability of E-cadherin junctions (2006) J. Biol. Chem., 281, pp. 23138-23149; Pinho, S.S., Reis, C.A., Paredes, J., Magalhaes, A.M., Ferreira, A.C., Figueiredo, J., Xiaogang, W., Seruca, R., The role of N-acetylglucosaminyltransferase III and V in the post-transcriptional modifications of E-cadherin (2009) Hum. Mol. Genet., 18, pp. 2599-2608; Pinho, S.S., Oliveira, P., Cabral, J., Carvalho, S., Huntsman, D., Gartner, F., Seruca, R., Oliveira, C., Loss and recovery of Mgat3 and GnT-III mediated E-cadherin N-glycosylation is a mechanism involved in epithelial-mesenchymal-epithelial transitions (2012) PLoS One, 7, pp. e33191; Osumi, D., Takahashi, M., Miyoshi, E., Yokoe, S., Lee, S.H., Noda, K., Nakamori, S., Taniguchi, N., Core fucosylation of E-cadherin enhances cell-cell adhesion in human colon carcinoma WiDr cells (2009) Cancer Sci., 100, pp. 888-895; Takeichi, M., Functional correlation between cell adhesive properties and some cell surface proteins (1977) J. Cell Biol., 75, pp. 464-474; Hyafil, F., Morello, D., Babinet, C., Jacob, F., A cell surface glycoprotein involved in the compaction of embryonal carcinoma cells and cleavage stage embryos (1980) Cell, 21, pp. 927-934; Ogou, S., Okada, T.S., Takeichi, M., Cleavage stage mouse embryos share a common cell adhesion system with teratocarcinoma cells (1982) Dev. Biol., 92, pp. 521-528; Takeichi, M., The cadherins: cell-cell adhesion molecules controlling animal morphogenesis (1988) Development, 102, pp. 639-655; Fleming, T.P., Javed, Q., Hay, M., Epithelial differentiation and intercellular junction formation in the mouse early embryo (1992) Dev. Suppl., pp. 105-112; Aplin, J.D., Jones, C.J., Harris, L.K., Adhesion molecules in human trophoblast-a review. I. Villous trophoblast (2009) Placenta, 30, pp. 293-298; Nose, A., Takeichi, M., A novel cadherin cell adhesion molecule: its expression patterns associated with implantation and organogenesis of mouse embryos (1986) J. Cell Biol., 103, pp. 2649-2658; Larue, L., Ohsugi, M., Hirchenhain, J., Kemler, R., E-cadherin null mutant embryos fail to form a trophectoderm epithelium (1994) Proc. Natl. Acad. Sci. U. S. A., 91, pp. 8263-8267; Riethmacher, D., Brinkmann, V., Birchmeier, C., A targeted mutation in the mouse E-cadherin gene results in defective preimplantation development (1995) Proc. Natl. Acad. Sci. U. S. A., 92, pp. 855-859; Radice, G.L., Ferreira-Cornwell, M.C., Robinson, S.D., Rayburn, H., Chodosh, L.A., Takeichi, M., Hynes, R.O., Precocious mammary gland development in P-cadherin-deficient mice (1997) J. Cell Biol., 139, pp. 1025-1032; Frebourg, T., Oliveira, C., Hochain, P., Karam, R., Manouvrier, S., Graziadio, C., Vekemans, M., Seruca, R., Cleft lip/palate and CDH1/E-cadherin mutations in families with hereditary diffuse gastric cancer (2006) J. Med. Genet., 43, pp. 138-142; Kjaer, K.W., Hansen, L., Schwabe, G.C., Marques-de-Faria, A.P., Eiberg, H., Mundlos, S., Tommerup, N., Rosenberg, T., Distinct CDH3 mutations cause ectodermal dysplasia, ectrodactyly, macular dystrophy (EEM syndrome) (2005) J. Med. Genet., 42, pp. 292-298; Sprecher, E., Bergman, R., Richard, G., Lurie, R., Shalev, S., Petronius, D., Shalata, A., Szargel, R., Hypotrichosis with juvenile macular dystrophy is caused by a mutation in CDH3, encoding P-cadherin (2001) Nat. Genet., 29, pp. 134-136; Nelson, W.J., Epithelial cell polarity from the outside looking in (2003) News Physiol. Sci., 18, pp. 143-146; Hirai, Y., Nose, A., Kobayashi, S., Takeichi, M., Expression and role of E- and P-cadherin adhesion molecules in embryonic histogenesis. II. Skin morphogenesis (1989) Development, 105, pp. 271-277; Berx, G., Van Roy, F., The E-cadherin/catenin complex: an important gatekeeper in breast cancer tumorigenesis and malignant progression (2001) Breast Cancer Res., 3, pp. 289-293; Shimoyama, Y., Hirohashi, S., Expression of E- and P-cadherin in gastric carcinomas (1991) Cancer Res., 51, pp. 2185-2192; Hines, M.D., Jin, H.C., Wheelock, M.J., Jensen, P.J., Inhibition of cadherin function differentially affects markers of terminal differentiation in cultured human keratinocytes (1999) J. Cell Sci., 112 (PART 24), pp. 4569-4579; Ribeiro, A.S., Albergaria, A., Sousa, B., Correia, A.L., Bracke, M., Seruca, R., Schmitt, F.C., Paredes, J., Extracellular cleavage and shedding of P-cadherin: a mechanism underlying the invasive behaviour of breast cancer cells (2010) Oncogene, 29, pp. 392-402; Moll, R., Mitze, M., Frixen, U.H., Birchmeier, W., Differential loss of E-cadherin expression in infiltrating ductal and lobular breast carcinomas (1993) Am. J. Pathol., 143, pp. 1731-1742; Gamallo, C., Palacios, J., Suarez, A., Pizarro, A., Navarro, P., Quintanilla, M., Cano, A., Correlation of E-cadherin expression with differentiation grade and histological type in breast carcinoma (1993) Am. J. Pathol., 142, pp. 987-993; Reis-Filho, J.S., Cancela Paredes, J., Milanezi, F., Schmitt, F.C., Clinicopathologic implications of E-cadherin reactivity in patients with lobular carcinoma in situ of the breast (2002) Cancer, 94, pp. 2114-2115; author reply 2115-2116Weigelt, B., Geyer, F.C., Natrajan, R., Lopez-Garcia, M.A., Ahmad, A.S., Savage, K., Kreike, B., Reis-Filho, J.S., The molecular underpinning of lobular histological growth pattern: a genome-wide transcriptomic analysis of invasive lobular carcinomas and grade- and molecular subtype-matched invasive ductal carcinomas of no special type (2010) J. Pathol., 220, pp. 45-57; Simpson, P.T., Reis-Filho, J.S., Lambros, M.B., Jones, C., Steele, D., Mackay, A., Iravani, M., Lakhani, S.R., Molecular profiling pleomorphic lobular carcinomas of the breast: evidence for a common molecular genetic pathway with classic lobular carcinomas (2008) J. Pathol., 215, pp. 231-244; Mahler-Araujo, B., Savage, K., Parry, S., Reis-Filho, J.S., Reduction of E-cadherin expression is associated with non-lobular breast carcinomas of basal-like and triple negative phenotype (2008) J. Clin. Pathol., 61, pp. 615-620; Lopes, N., Carvalho, J., Duraes, C., Sousa, B., Gomes, M., Costa, J.L., Oliveira, C., Schmitt, F., 1Alpha,25-dihydroxyvitamin D3 induces de novo E-cadherin expression in triple-negative breast cancer cells by CDH1-promoter demethylation (2012) Anticancer. Res., 32, pp. 249-257; Berx, G., Cleton-Jansen, A.M., Strumane, K., de Leeuw, W.J., Nollet, F., van Roy, F., Cornelisse, C., E-cadherin is inactivated in a majority of invasive human lobular breast cancers by truncation mutations throughout its extracellular domain (1996) Oncogene, 13, pp. 1919-1925; Keller, G., Vogelsang, H., Becker, I., Hutter, J., Ott, K., Candidus, S., Grundei, T., Hofler, H., Diffuse type gastric and lobular breast carcinoma in a familial gastric cancer patient with an E-cadherin germline mutation (1999) Am. J. Pathol., 155, pp. 337-342; Schrader, K.A., Masciari, S., Boyd, N., Wiyrick, S., Kaurah, P., Senz, J., Burke, W., Huntsman, D.G., Hereditary diffuse gastric cancer: association with lobular breast cancer (2008) Fam. Cancer, 7, pp. 73-82; Becker, K.F., Atkinson, M.J., Reich, U., Becker, I., Nekarda, H., Siewert, J.R., Hofler, H., E-cadherin gene mutations provide clues to diffuse type gastric carcinomas (1994) Cancer Res., 54, pp. 3845-3852; Becker, K.F., Kremmer, E., Eulitz, M., Becker, I., Handschuh, G., Schuhmacher, C., Muller, W., Hofler, H., Analysis of E-cadherin in diffuse-type gastric cancer using a mutation-specific monoclonal antibody (1999) Am. J. Pathol., 155, pp. 1803-1809; Machado, J.C., Carneiro, F., Beck, S., Rossi, S., Lopes, J., Taveira-Gomes, A., Cardoso-Oliveira, M., E-cadherin expression is correlated with the isolated cell/diffuse histotype and with features of biological aggressiveness of gastric carcinoma (1998) Int. J. Surg. Pathol., 6, pp. 135-144; Carneiro, F., Machado, J.C., Seruca, R., Sobrinho-Simoes, M., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Carvalho, J., van Grieken, N.C., Pereira, P.M., Sousa, S., Tijssen, M., Buffart, T.E., Diosdado, B., Oliveira, C., Lack of microRNA-101 causes E-cadherin functional deregulation through EZH2 upregulation in intestinal gastric cancer (2012) J. Pathol.; Machado, J.C., Oliveira, C., Carvalho, R., Soares, P., Berx, G., Caldas, C., Seruca, R., Sobrinho-Simoes, M., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Guilford, P., Hopkins, J., Harraway, J., McLeod, M., McLeod, N., Harawira, P., Taite, H., Reeve, A.E., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 392, pp. 402-405; Oliveira, C., Senz, J., Kaurah, P., Pinheiro, H., Sanges, R., Haegert, A., Corso, G., Huntsman, D., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum. Mol. Genet., 18, pp. 1545-1555; Pinheiro, H., Bordeira-Carrico, R., Seixas, S., Carvalho, J., Senz, J., Oliveira, P., Inacio, P., Oliveira, C., Allele-specific CDH1 downregulation and hereditary diffuse gastric cancer (2010) Hum. Mol. Genet., 19, pp. 943-952; Guilford, P., Humar, B., Blair, V., Hereditary diffuse gastric cancer: translation of CDH1 germline mutations into clinical practice (2010) Gastric Cancer, 13, pp. 1-10; Suriano, G., Seixas, S., Rocha, J., Seruca, R., A model to infer the pathogenic significance of CDH1 germline missense variants (2006) J. Mol. Med., 84, pp. 1023-1031; Suriano, G., Oliveira, C., Ferreira, P., Machado, J.C., Bordin, M.C., De Wever, O., Bruyneel, E.A., Seruca, R., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum. Mol. Genet., 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., Mateus, A.R., Ferreira, P., Casares, F., Oliveira, C., Seruca, R., E-cadherin germline missense mutations and cell phenotype: evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum. Mol. Genet., 12, pp. 3007-3016; Brooks-Wilson, A.R., Kaurah, P., Suriano, G., Leach, S., Senz, J., Grehan, N., Butterfield, Y.S., Huntsman, D., Germline E-cadherin mutations in hereditary diffuse gastric cancer: assessment of 42 new families and review of genetic screening criteria (2004) J. Med. Genet., 41, pp. 508-517; Kaurah, P., MacMillan, A., Boyd, N., Senz, J., De Luca, A., Chun, N., Suriano, G., Huntsman, D., Founder and recurrent CDH1 mutations in families with hereditary diffuse gastric cancer (2007) JAMA, 297, pp. 2360-2372; Corso, G., Roviello, F., Paredes, J., Pedrazzani, C., Novais, M., Correia, J., Marrelli, D., Suriano, G., Characterization of the P373L E-cadherin germline missense mutation and implication for clinical management (2007) Eur. J. Surg. Oncol., 33, pp. 1061-1067; More, H., Humar, B., Weber, W., Ward, R., Christian, A., Lintott, C., Graziano, F., Guilford, P., Identification of seven novel germline mutations in the human E-cadherin (CDH1) gene (2007) Hum. Mutat., 28, p. 203; Oliveira, C., de Bruin, J., Nabais, S., Ligtenberg, M., Moutinho, C., Nagengast, F.M., Seruca, R., Carneiro, F., Intragenic deletion of CDH1 as the inactivating mechanism of the wild-type allele in an HDGC tumour (2004) Oncogene, 23, pp. 2236-2240; Barber, M., Murrell, A., Ito, Y., Maia, A.T., Hyland, S., Oliveira, C., Save, V., Fitzgerald, R.C., Mechanisms and sequelae of E-cadherin silencing in hereditary diffuse gastric cancer (2008) J. Pathol., 216, pp. 295-306; Oliveira, C., Sousa, S., Pinheiro, H., Karam, R., Bordeira-Carrico, R., Senz, J., Kaurah, P., Seruca, R., Quantification of epigenetic and genetic 2nd hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Grady, W.M., Willis, J., Guilford, P.J., Dunbier, A.K., Toro, T.T., Lynch, H., Wiesner, G., Markowitz, S., Methylation of the CDH1 promoter as the second genetic hit in hereditary diffuse gastric cancer (2000) Nat. Genet., 26, pp. 16-17; Peinado, H., Ballestar, E., Esteller, M., Cano, A., Snail mediates E-cadherin repression by the recruitment of the Sin3A/histone deacetylase 1 (HDAC1)/HDAC2 complex (2004) Mol. Cell. Biol., 24, pp. 306-319; Fujii, S., Ochiai, A., Enhancer of zeste homolog 2 downregulates E-cadherin by mediating histone H3 methylation in gastric cancer cells (2008) Cancer Sci., 99, pp. 738-746; Cao, Q., Yu, J., Dhanasekaran, S.M., Kim, J.H., Mani, R.S., Tomlins, S.A., Mehra, R., Chinnaiyan, A.M., Repression of E-cadherin by the polycomb group protein EZH2 in cancer (2008) Oncogene, 27, pp. 7274-7284; Pena, C., Garcia, J.M., Silva, J., Garcia, V., Rodriguez, R., Alonso, I., Millan, I., Bonilla, F., E-cadherin and vitamin D receptor regulation by SNAIL and ZEB1 in colon cancer: clinicopathological correlations (2005) Hum. Mol. Genet., 14, pp. 3361-3370; Liu, Y., Hong, Y., Zhao, Y., Ismail, T.M., Wong, Y., Eu, K.W., Histone H3 (lys-9) deacetylation is associated with transcriptional silencing of E-cadherin in colorectal cancer cell lines (2008) Cancer Invest., 26, pp. 575-582; von Burstin, J., Eser, S., Paul, M.C., Seidler, B., Brandl, M., Messer, M., von Werder, A., Saur, D., E-cadherin regulates metastasis of pancreatic cancer in vivo and is suppressed by a SNAIL/HDAC1/HDAC2 repressor complex (2009) Gastroenterology, 137, pp. 361-371. , (371 e361-365); Herranz, N., Pasini, D., Diaz, V.M., Franci, C., Gutierrez, A., Dave, N., Escriva, M., Peiro, S., Polycomb complex 2 is required for E-cadherin repression by the Snail1 transcription factor (2008) Mol. Cell. Biol., 28, pp. 4772-4781; Ambros, V., The functions of animal microRNAs (2004) Nature, 431, pp. 350-355; He, L., Hannon, G.J., MicroRNAs: small RNAs with a big role in gene regulation (2004) Nat. Rev. Genet., 5, pp. 522-531; Hurteau, G.J., Carlson, J.A., Spivack, S.D., Brock, G.J., Overexpression of the microRNA hsa-miR-200c leads to reduced expression of transcription factor 8 and increased expression of E-cadherin (2007) Cancer Res., 67, pp. 7972-7976; Korpal, M., Lee, E.S., Hu, G., Kang, Y., The miR-200 family inhibits epithelial-mesenchymal transition and cancer cell migration by direct targeting of E-cadherin transcriptional repressors ZEB1 and ZEB2 (2008) J. Biol. Chem., 283, pp. 14910-14914; Gregory, P.A., Bert, A.G., Paterson, E.L., Barry, S.C., Tsykin, A., Farshid, G., Vadas, M.A., Goodall, G.J., The miR-200 family and miR-205 regulate epithelial to mesenchymal transition by targeting ZEB1 and SIP1 (2008) Nat. Cell Biol., 10, pp. 593-601; Park, S.M., Gaur, A.B., Lengyel, E., Peter, M.E., The miR-200 family determines the epithelial phenotype of cancer cells by targeting the E-cadherin repressors ZEB1 and ZEB2 (2008) Genes Dev., 22, pp. 894-907; Tan, H.X., Wang, Q., Chen, L.Z., Huang, X.H., Chen, J.S., Fu, X.H., Cao, L.Q., Zhang, L.J., MicroRNA-9 reduces cell invasion and E-cadherin secretion in SK-Hep-1 cell (2010) Med. Oncol., 27, pp. 654-660; Ma, L., Young, J., Prabhala, H., Pan, E., Mestdagh, P., Muth, D., Teruya-Feldstein, J., Weinberg, R.A., MiR-9, a MYC/MYCN-activated microRNA, regulates E-cadherin and cancer metastasis (2010) Nat. Cell Biol., 12, pp. 247-256; Oki, Y., Issa, J.P., Epigenetic mechanisms in AML-a target for therapy (2010) Cancer Treat. Res., 145, pp. 19-40; Simoes-Correia, J., Figueiredo, J., Oliveira, C., van Hengel, J., Seruca, R., van Roy, F., Suriano, G., Endoplasmic reticulum quality control: a new mechanism of E-cadherin regulation and its implication in cancer (2008) Hum. Mol. Genet., 17, pp. 3566-3576; Sitia, R., Braakman, I., Quality control in the endoplasmic reticulum protein factory (2003) Nature, 426, pp. 891-894; Meusser, B., Hirsch, C., Jarosch, E., Sommer, T., ERAD: the long road to destruction (2005) Nat. Cell Biol., 7, pp. 766-772; van Hengel, J., van Roy, F., Diverse functions of p120ctn in tumors (2007) Biochim. Biophys. Acta, 1773, pp. 78-88; Jawhari, A.U., Noda, M., Pignatelli, M., Farthing, M., Up-regulated cytoplasmic expression, with reduced membranous distribution, of the src substrate p120(ctn) in gastric carcinoma (1999) J. Pathol., 189, pp. 180-185; Karayiannakis, A.J., Syrigos, K.N., Alexiou, D., Kalahanis, N., Rosenberg, T., Bastounis, E., Pignatelli, M., Expression patterns of the novel catenin p120cas in gastrointestinal cancers (1999) Anticancer. Res., 19, pp. 4401-4405; Karatzas, G., Karayiannakis, A.J., Syrigos, K.N., Chatzigianni, E., Papanikolaou, S., Simatos, G., Papanikolaou, D., Bogris, S., Expression patterns of the E-cadherin-catenin cell-cell adhesion complex in gastric cancer (2000) Hepatogastroenterology, 47, pp. 1465-1469; Apweiler, R., Hermjakob, H., Sharon, N., On the frequency of protein glycosylation, as deduced from analysis of the SWISS-PROT database (1999) Biochim. Biophys. Acta, 1473, pp. 4-8; Dube, D.H., Bertozzi, C.R., Glycans in cancer and inflammation-potential for therapeutics and diagnostics (2005) Nat. Rev. Drug Discov., 4, pp. 477-488; Pinho, S.S., Osorio, H., Nita-Lazar, M., Gomes, J., Lopes, C., Gartner, F., Reis, C.A., Role of E-cadherin N-glycosylation profile in a mammary tumor model (2009) Biochem. Biophys. Res. Commun., 379, pp. 1091-1096; Iijima, J., Zhao, Y., Isaji, T., Kameyama, A., Nakaya, S., Wang, X., Ihara, H., Gu, J., Cell-cell interaction-dependent regulation of N-acetylglucosaminyltransferase III and the bisected N-glycans in GE11 epithelial cells. Involvement of E-cadherin-mediated cell adhesion (2006) J. Biol. Chem., 281, pp. 13038-13046; Yoshimura, M., Ihara, Y., Matsuzawa, Y., Taniguchi, N., Aberrant glycosylation of E-cadherin enhances cell-cell binding to suppress metastasis (1996) J. Biol. Chem., 271, pp. 13811-13815; Giles, R.H., van Es, J.H., Clevers, H., Caught up in a Wnt storm: Wnt signaling in cancer (2003) Biochim. Biophys. Acta, 1653, pp. 1-24; Reynolds, A.B., Roczniak-Ferguson, A., Emerging roles for p120-catenin in cell adhesion and cancer (2004) Oncogene, 23, pp. 7947-7956; Christofori, G., Changing neighbours, changing behaviour: cell adhesion molecule-mediated signalling during tumour progression (2003) EMBO J., 22, pp. 2318-2323; Gottardi, C.J., Wong, E., Gumbiner, B.M., E-cadherin suppresses cellular transformation by inhibiting beta-catenin signaling in an adhesion-independent manner (2001) J. Cell Biol., 153, pp. 1049-1060; Stockinger, A., Eger, A., Wolf, J., Beug, H., Foisner, R., E-cadherin regulates cell growth by modulating proliferation-dependent beta-catenin transcriptional activity (2001) J. Cell Biol., 154, pp. 1185-1196; Suriano, G., Mulholland, D., de Wever, O., Ferreira, P., Mateus, A.R., Bruyneel, E., Nelson, C.C., Seruca, R., The intracellular E-cadherin germline mutation V832 M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Sahai, E., Marshall, C.J., RHO-GTPases and cancer (2002) Nat. Rev. Cancer, 2, pp. 133-142; Deplazes, J., Fuchs, M., Rauser, S., Genth, H., Lengyel, E., Busch, R., Luber, B., Rac1 and Rho contribute to the migratory and invasive phenotype associated with somatic E-cadherin mutation (2009) Hum. Mol. Genet., 18, pp. 3632-3644; Mateus, A.R., Seruca, R., Machado, J.C., Keller, G., Oliveira, M.J., Suriano, G., Luber, B., EGFR regulates RhoA-GTP dependent cell motility in E-cadherin mutant cells (2007) Hum. Mol. Genet., 16, pp. 1639-1647; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., Heindl, S., Alves, C.C., Suriano, G., Luber, B., Seruca, R., E-cadherin mutations and cell motility: a genotype-phenotype correlation (2009) Exp. Cell Res., 315, pp. 1393-1402; Crepaldi, T., Pollack, A.L., Prat, M., Zborek, A., Mostov, K., Comoglio, P.M., Targeting of the SF/HGF receptor to the basolateral domain of polarized epithelial cells (1994) J. Cell Biol., 125, pp. 313-320; Pece, S., Gutkind, J.S., Signaling from E-cadherins to the MAPK pathway by the recruitment and activation of epidermal growth factor receptors upon cell-cell contact formation (2000) J. Biol. Chem., 275, pp. 41227-41233; Thiery, J.P., Epithelial-mesenchymal transitions in tumour progression (2002) Nat. Rev. Cancer, 2, pp. 442-454; Qian, X., Karpova, T., Sheppard, A.M., McNally, J., Lowy, D.R., E-cadherin-mediated adhesion inhibits ligand-dependent activation of diverse receptor tyrosine kinases (2004) EMBO J., 23, pp. 1739-1748; Takahashi, K., Suzuki, K., Density-dependent inhibition of growth involves prevention of EGF receptor activation by E-cadherin-mediated cell-cell adhesion (1996) Exp. Cell Res., 226, pp. 214-222; Mook, O.R., Frederiks, W.M., Van Noorden, C.J., The role of gelatinases in colorectal cancer progression and metastasis (2004) Biochim. Biophys. Acta, 1705, pp. 69-89; Munshi, H.G., Ghosh, S., Mukhopadhyay, S., Wu, Y.I., Sen, R., Green, K.J., Stack, M.S., Proteinase suppression by E-cadherin-mediated cell-cell attachment in premalignant oral keratinocytes (2002) J. Biol. Chem., 277, pp. 38159-38167; Lochter, A., Galosy, S., Muschler, J., Freedman, N., Werb, Z., Bissell, M.J., Matrix metalloproteinase stromelysin-1 triggers a cascade of molecular alterations that leads to stable epithelial-to-mesenchymal conversion and a premalignant phenotype in mammary epithelial cells (1997) J. Cell Biol., 139, pp. 1861-1872; Davies, G., Jiang, W.G., Mason, M.D., Matrilysin mediates extracellular cleavage of E-cadherin from prostate cancer cells: a key mechanism in hepatocyte growth factor/scatter factor-induced cell-cell dissociation and in vitro invasion (2001) Clin. Cancer Res., 7, pp. 3289-3297; Noe, V., Fingleton, B., Jacobs, K., Crawford, H.C., Vermeulen, S., Steelant, W., Bruyneel, E., Mareel, M., Release of an invasion promoter E-cadherin fragment by matrilysin and stromelysin-1 (2001) J. Cell Sci., 114, pp. 111-118; Ryniers, F., Stove, C., Goethals, M., Brackenier, L., Noe, V., Bracke, M., Vandekerckhove, J., Bruyneel, E., Plasmin produces an E-cadherin fragment that stimulates cancer cell invasion (2002) Biol. Chem., 383, pp. 159-165; Comoglio, P.M., Boccaccio, C., Trusolino, L., Interactions between growth factor receptors and adhesion molecules: breaking the rules (2003) Curr. Opin. Cell Biol., 15, pp. 565-571; Ferreira, P., Oliveira, M.J., Beraldi, E., Mateus, A.R., Nakajima, T., Gleave, M., Yokota, J., Suriano, G., Loss of functional E-cadherin renders cells more resistant to the apoptotic agent taxol in vitro (2005) Exp. Cell Res., 310, pp. 99-104; Ferreira, A.C., Suriano, G., Mendes, N., Gomes, B., Wen, X., Carneiro, F., Seruca, R., Machado, J.C., E-cadherin impairment increases cell survival through Notch-dependent upregulation of Bcl-2 (2012) Hum. Mol. Genet., 21, pp. 334-343; Huang, F.Y., Chan, A.O., Rashid, A., Wong, D.K., Cho, C.H., Yuen, M.F., Helicobacter pylori induces promoter methylation of E-cadherin via interleukin-1beta activation of nitric oxide production in gastric cancer cells (2012) Cancer; Chan, A.O., Lam, S.K., Wong, B.C., Wong, W.M., Yuen, M.F., Yeung, Y.H., Hui, W.M., Kwong, Y.L., Promoter methylation of E-cadherin gene in gastric mucosa associated with Helicobacter pylori infection and in gastric cancer (2003) Gut, 52, pp. 502-506; Leung, W.K., Man, E.P., Yu, J., Go, M.Y., To, K.F., Yamaoka, Y., Cheng, V.Y., Sung, J.J., Effects of Helicobacter pylori eradication on methylation status of E-cadherin gene in noncancerous stomach (2006) Clin. Cancer Res., 12, pp. 3216-3221; Perri, F., Cotugno, R., Piepoli, A., Merla, A., Quitadamo, M., Gentile, A., Pilotto, A., Andriulli, A., Aberrant DNA methylation in non-neoplastic gastric mucosa of H. pylori infected patients and effect of eradication (2007) Am. J. Gastroenterol., 102, pp. 1361-1371; Chan, A.O., Peng, J.Z., Lam, S.K., Lai, K.C., Yuen, M.F., Cheung, H.K., Kwong, Y.L., Wong, B.C., Eradication of Helicobacter pylori infection reverses E-cadherin promoter hypermethylation (2006) Gut, 55, pp. 463-468; Schirrmeister, W., Gnad, T., Wex, T., Higashiyama, S., Wolke, C., Naumann, M., Lendeckel, U., Ectodomain shedding of E-cadherin and c-Met is induced by Helicobacter pylori infection (2009) Exp. Cell Res., 315, pp. 3500-3508; Hoy, B., Lower, M., Weydig, C., Carra, G., Tegtmeyer, N., Geppert, T., Schroder, P., Wessler, S., Helicobacter pylori HtrA is a new secreted virulence factor that cleaves E-cadherin to disrupt intercellular adhesion (2010) EMBO Rep., 11, pp. 798-804; O'Connor, P.M., Lapointe, T.K., Jackson, S., Beck, P.L., Jones, N.L., Buret, A.G., Helicobacter pylori activates calpain via toll-like receptor 2 to disrupt adherens junctions in human gastric epithelial cells (2011) Infect. Immun., 79, pp. 3887-3894; Conlin, V.S., Curtis, S.B., Zhao, Y., Moore, E.D., Smith, V.C., Meloche, R.M., Finlay, B.B., Buchan, A.M., Helicobacter pylori infection targets adherens junction regulatory proteins and results in increased rates of migration in human gastric epithelial cells (2004) Infect. Immun., 72, pp. 5181-5192; Suzuki, M., Mimuro, H., Suzuki, T., Park, M., Yamamoto, T., Sasakawa, C., Interaction of CagA with Crk plays an important role in Helicobacter pylori-induced loss of gastric epithelial cell adhesion (2005) J. Exp. Med., 202, pp. 1235-1247; Franco, A.T., Israel, D.A., Washington, M.K., Krishna, U., Fox, J.G., Rogers, A.B., Neish, A.S., Peek, R.M., Activation of beta-catenin by carcinogenic Helicobacter pylori (2005) Proc. Natl. Acad. Sci. U. S. A., 102, pp. 10646-10651; Murata-Kamiya, N., Kurashima, Y., Teishikata, Y., Yamahashi, Y., Saito, Y., Higashi, H., Aburatani, H., Hatakeyama, M., Helicobacter pylori CagA interacts with E-cadherin and deregulates the beta-catenin signal that promotes intestinal transdifferentiation in gastric epithelial cells (2007) Oncogene, 26, pp. 4617-4626; Sokolova, O., Bozko, P.M., Naumann, M., Helicobacter pylori suppresses glycogen synthase kinase 3beta to promote beta-catenin activity (2008) J. Biol. Chem., 283, pp. 29367-29374; Ogden, S.R., Wroblewski, L.E., Weydig, C., Romero-Gallo, J., O'Brien, D.P., Israel, D.A., Krishna, U.S., Peek, R.M., P120 and Kaiso regulate Helicobacter pylori-induced expression of matrix metalloproteinase-7 (2008) Mol. Biol. Cell, 19, pp. 4110-4121; Bebb, J.R., Leach, L., Zaitoun, A., Hand, N., Letley, D.P., Thomas, R., Atherton, J.C., Effects of Helicobacter pylori on the cadherin-catenin complex (2006) J. Clin. Pathol., 59, pp. 1261-1266; Oliveira, M.J., Costa, A.M., Costa, A.C., Ferreira, R.M., Sampaio, P., Machado, J.C., Seruca, R., Figueiredo, C., CagA associates with c-Met, E-cadherin, and p120-catenin in a multiproteic complex that suppresses Helicobacter pylori-induced cell-invasive phenotype (2009) J. Infect. Dis., 200, pp. 745-755; Oliveira, M.J., Costa, A.C., Costa, A.M., Henriques, L., Suriano, G., Atherton, J.C., Machado, J.C., Figueiredo, C., Helicobacter pylori induces gastric epithelial cell invasion in a c-Met and type IV secretion system-dependent manner (2006) J. Biol. Chem., 281, pp. 34888-34896; Jang, A.C., Starz-Gaiano, M., Montell, D.J., Modeling migration and metastasis in Drosophila (2007) J. Mammary Gland Biol. Neoplasia, 12, pp. 103-114; Pereira, P.S., Teixeira, A., Pinho, S., Ferreira, P., Fernandes, J., Oliveira, C., Seruca, R., Casares, F., E-cadherin missense mutations, associated with hereditary diffuse gastric cancer (HDGC) syndrome, display distinct invasive behaviors and genetic interactions with the Wnt and Notch pathways in Drosophila epithelia (2006) Hum. Mol. Genet., 15, pp. 1704-1712; Caldeira, J., Pereira, P.S., Suriano, G., Casares, F., Using fruitflies to help understand the molecular mechanisms of human hereditary diffuse gastric cancer (2009) Int. J. Dev. Biol., 53, pp. 1557-1561; Humar, B., Blair, V., Charlton, A., More, H., Martin, I., Guilford, P., E-cadherin deficiency initiates gastric signet-ring cell carcinoma in mice and man (2009) Cancer Res., 69, pp. 2050-2056; Mbalaviele, G., Dunstan, C.R., Sasaki, A., Williams, P.J., Mundy, G.R., Yoneda, T., E-cadherin expression in human breast cancer cells suppresses the development of osteolytic bone metastases in an experimental metastasis model (1996) Cancer Res., 56, pp. 4063-4070; Perl, A.K., Wilgenbus, P., Dahl, U., Semb, H., Christofori, G., A causal role for E-cadherin in the transition from adenoma to carcinoma (1998) Nature, 392, pp. 190-193; Kuwabara, Y., Yamada, T., Yamazaki, K., Du, W.L., Banno, K., Aoki, D., Sakamoto, M., Establishment of an ovarian metastasis model and possible involvement of E-cadherin down-regulation in the metastasis (2008) Cancer Sci., 99, pp. 1933-1939; Shimoyama, Y., Hirohashi, S., Hirano, S., Noguchi, M., Shimosato, Y., Takeichi, M., Abe, O., Cadherin cell-adhesion molecules in human epithelial tissues and carcinomas (1989) Cancer Res., 49, pp. 2128-2133; Sanders, D.S., Bruton, R., Darnton, S.J., Casson, A.G., Hanson, I., Williams, H.K., Jankowski, J., Sequential changes in cadherin-catenin expression associated with the progression and heterogeneity of primary oesophageal squamous carcinoma (1998) Int. J. Cancer, 79, pp. 573-579; Rocha, A.S., Soares, P., Machado, J.C., Maximo, V., Fonseca, E., Franssila, K., Sobrinho-Simoes, M., Mucoepidermoid carcinoma of the thyroid: a tumour histotype characterised by P-cadherin neoexpression and marked abnormalities of E-cadherin/catenins complex (2002) Virchows Arch., 440, pp. 498-504; Kim, M.A., Jung, E.J., Lee, H.S., Lee, H.E., Yang, H.K., Oh, D.Y., Bang, Y.J., Kim, W.H., P-cadherin expression in gastric carcinoma: its regulation mechanism and prognostic significance (2010) Hum. Pathol., 41, pp. 877-885; Imai, K., Hirata, S., Irie, A., Senju, S., Ikuta, Y., Yokomine, K., Harao, M., Nishimura, Y., Identification of a novel tumor-associated antigen, cadherin 3/P-cadherin, as a possible target for immunotherapy of pancreatic, gastric, and colorectal cancers (2008) Clin. Cancer Res., 14, pp. 6487-6495; Lo Muzio, L., Campisi, G., Farina, A., Rubini, C., Pannone, G., Serpico, R., Laino, G., Carinci, F., P-cadherin expression and survival rate in oral squamous cell carcinoma: an immunohistochemical study (2005) BMC Cancer, 5, p. 63; Han, A.C., Edelson, M.I., Peralta Soler, A., Knudsen, K.A., Lifschitz-Mercer, B., Czernobilsky, B., Rosenblum, N.G., Salazar, H., Cadherin expression in glandular tumors of the cervix (2000) Cancer, 89, pp. 2053-2058; Longatto Filho, A., Albergaria, A., Paredes, J., Moreira, M.A., Milanezi, F., Schmitt, F.C., P-cadherin expression in glandular lesions of the uterine cervix detected by liquid-based cytology (2005) Cytopathology, 16, pp. 88-93; Stefansson, I.M., Salvesen, H.B., Akslen, L.A., Prognostic impact of alterations in P-cadherin expression and related cell adhesion markers in endometrial cancer (2004) J. Clin. Oncol., 22, pp. 1242-1252; Moreno-Bueno, G., Hardisson, D., Sarrio, D., Sanchez, C., Cassia, R., Prat, J., Herman, J.G., Palacios, J., Abnormalities of E- and P-cadherin and catenin (beta-, gamma-catenin, and p120ctn) expression in endometrial cancer and endometrial atypical hyperplasia (2003) J. Pathol., 199, pp. 471-478; Quattrocchi, L., Green, A.R., Martin, S., Durrant, L., Deen, S., The cadherin switch in ovarian high-grade serous carcinoma is associated with disease progression (2011) Virchows Arch., 459, pp. 21-29; Sarrio, D., Moreno-Bueno, G., Sanchez-Estevez, C., Banon-Rodriguez, I., Hernandez-Cortes, G., Hardisson, D., Palacios, J., Expression of cadherins and catenins correlates with distinct histologic types of ovarian carcinomas (2006) Hum. Pathol., 37, pp. 1042-1049; Soler, A.P., Harner, G.D., Knudsen, K.A., McBrearty, F.X., Grujic, E., Salazar, H., Han, A.C., Keshgegian, A.A., Expression of P-cadherin identifies prostate-specific-antigen-negative cells in epithelial tissues of male sexual accessory organs and in prostatic carcinomas. Implications for prostate cancer biology (1997) Am. J. Pathol., 151, pp. 471-478; Bryan, R.T., Atherfold, P.A., Yeo, Y., Jones, L.J., Harrison, R.F., Wallace, D.M., Jankowski, J.A., Cadherin switching dictates the biology of transitional cell carcinoma of the bladder: ex vivo and in vitro studies (2008) J. Pathol., 215, pp. 184-194; Matos, I., Dufloth, R., Alvarenga, M., Zeferino, L.C., Schmitt, F., P63, cytokeratin 5, and P-cadherin: three molecular markers to distinguish basal phenotype in breast carcinomas (2005) Virchows Arch., 447, pp. 688-694; Arnes, J.B., Brunet, J.S., Stefansson, I., Begin, L.R., Wong, N., Chappuis, P.O., Akslen, L.A., Foulkes, W.D., Placental cadherin and the basal epithelial phenotype of BRCA1-related breast cancer (2005) Clin. Cancer Res., 11, pp. 4003-4011; Palacios, J., Benito, N., Pizarro, A., Suarez, A., Espada, J., Cano, A., Gamallo, C., Anomalous expression of P-cadherin in breast carcinoma. Correlation with E-cadherin expression and pathological features (1995) Am. J. Pathol., 146, pp. 605-612; Peralta Soler, A., Knudsen, K.A., Salazar, H., Han, A.C., Keshgegian, A.A., P-cadherin expression in breast carcinoma indicates poor survival (1999) Cancer, 86, pp. 1263-1272; Paredes, J., Milanezi, F., Reis-Filho, J.S., Leitao, D., Athanazio, D., Schmitt, F., Aberrant P-cadherin expression: is it associated with estrogen-independent growth in breast cancer? (2002) Pathol. Res. Pract., 198, pp. 795-801; Kovacs, A., Dhillon, J., Walker, R.A., Expression of P-cadherin, but not E-cadherin or N-cadherin, relates to pathological and functional differentiation of breast carcinomas (2003) Mol. Pathol., 56, pp. 318-322; Gamallo, C., Moreno-Bueno, G., Sarrio, D., Calero, F., Hardisson, D., Palacios, J., The prognostic significance of P-cadherin in infiltrating ductal breast carcinoma (2001) Mod. Pathol., 14, pp. 650-654; Paredes, J., Correia, A.L., Ribeiro, A.S., Milanezi, F., Cameselle-Teijeiro, J., Schmitt, F.C., Breast carcinomas that co-express E- and P-cadherin are associated with p120-catenin cytoplasmic localisation and poor patient survival (2008) J. Clin. Pathol., 61, pp. 856-862; Foulkes, W.D., Stefansson, I.M., Chappuis, P.O., Begin, L.R., Goffin, J.R., Wong, N., Trudel, M., Akslen, L.A., Germline BRCA1 mutations and a basal epithelial phenotype in breast cancer (2003) J. Natl. Cancer Inst., 95, pp. 1482-1485; Lakhani, S.R., Reis-Filho, J.S., Fulford, L., Penault-Llorca, F., van der Vijver, M., Parry, S., Bishop, T., Easton, D.F., Prediction of BRCA1 status in patients with breast cancer using estrogen receptor and basal phenotype (2005) Clin. Cancer Res., 11, pp. 5175-5180; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Immunohistochemical characteristics defined by tissue microarray of hereditary breast cancer not attributable to BRCA1 or BRCA2 mutations: differences from breast carcinomas arising in BRCA1 and BRCA2 mutation carriers (2003) Clin. Cancer Res., 9, pp. 3606-3614; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Phenotypic characterization of BRCA1 and BRCA2 tumors based in a tissue microarray study with 37 immunohistochemical markers (2005) Breast Cancer Res. Treat., 90, pp. 5-14; Gorski, J.J., James, C.R., Quinn, J.E., Stewart, G.E., Staunton, K.C., Buckley, N.E., McDyer, F.A., Harkin, D.P., BRCA1 transcriptionally regulates genes associated with the basal-like phenotype in breast cancer (2010) Breast Cancer Res. Treat., 122, pp. 721-731; Albergaria, A., Ribeiro, A.S., Pinho, S., Milanezi, F., Carneiro, V., Sousa, B., Sousa, S., Schmitt, F., ICI 182,780 induces P-cadherin overexpression in breast cancer cells through chromatin remodelling at the promoter level: a role for C/EBPbeta in CDH3 gene activation (2010) Hum. Mol. Genet., 19, pp. 2554-2566; Sato, N., Fukushima, N., Maitra, A., Matsubayashi, H., Yeo, C.J., Cameron, J.L., Hruban, R.H., Goggins, M., Discovery of novel targets for aberrant methylation in pancreatic carcinoma using high-throughput microarrays (2003) Cancer Res., 63, pp. 3735-3742; Milicic, A., Harrison, L.A., Goodlad, R.A., Hardy, R.G., Nicholson, A.M., Presz, M., Sieber, O., Jankowski, J.A., Ectopic expression of P-cadherin correlates with promoter hypomethylation early in colorectal carcinogenesis and enhanced intestinal crypt fission in vivo (2008) Cancer Res., 68, pp. 7760-7768; Van Marck, V., Stove, C., Van Den Bossche, K., Stove, V., Paredes, J., Vander Haeghen, Y., Bracke, M., P-cadherin promotes cell-cell adhesion and counteracts invasion in human melanoma (2005) Cancer Res., 65, pp. 8774-8783; Sarrio, D., Palacios, J., Hergueta-Redondo, M., Gomez-Lopez, G., Cano, A., Moreno-Bueno, G., Functional characterization of E- and P-cadherin in invasive breast cancer cells (2009) BMC Cancer, 9, p. 74; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R.J., P-cadherin induces an epithelial-like phenotype in oral squamous cell carcinoma by GSK-3beta-mediated Snail phosphorylation (2009) Carcinogenesis, 30, pp. 1781-1788; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R., Slit-2 facilitates interaction of P-cadherin with Robo-3 and inhibits cell migration in an oral squamous cell carcinoma cell line (2011) Carcinogenesis, 32, pp. 935-943; Mandeville, J.A., Silva Neto, B., Vanni, A.J., Smith, G.L., Rieger-Christ, K.M., Zeheb, R., Loda, M., Summerhayes, I.C., P-cadherin as a prognostic indicator and a modulator of migratory behaviour in bladder carcinoma cells (2008) BJU Int., 102, pp. 1707-1714; Cheung, L.W., Leung, P.C., Wong, A.S., Cadherin switching and activation of p120 catenin signaling are mediators of gonadotropin-releasing hormone to promote tumor cell migration and invasion in ovarian cancer (2010) Oncogene, 29, pp. 2427-2440; Reynolds, A.B., Daniel, J.M., Mo, Y.Y., Wu, J., Zhang, Z., The novel catenin p120cas binds classical cadherins and induces an unusual morphological phenotype in NIH3T3 fibroblasts (1996) Exp. Cell Res., 225, pp. 328-337; Baki, L., Marambaud, P., Efthimiopoulos, S., Georgakopoulos, A., Wen, P., Cui, W., Shioi, J., Robakis, N.K., Presenilin-1 binds cytoplasmic epithelial cadherin, inhibits cadherin/p120 association, and regulates stability and function of the cadherin/catenin adhesion complex (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 2381-2386; Jacobs, K., Van Gele, M., Forsyth, R., Brochez, L., Vanhoecke, B., De Wever, O., Bracke, M., P-cadherin counteracts myosin II-B function: implications in melanoma progression (2010) Mol. Cancer, 9, p. 255; Radice, G.L., Sauer, C.L., Kostetskii, I., Peralta Soler, A., Knudsen, K.A., Inappropriate P-cadherin expression in the mouse mammary epithelium is compatible with normal mammary gland function (2003) Differentiation, 71, pp. 361-373; Gregory, D.J., Mikhaylova, L., Fedulov, A.V., Selective DNA demethylation by fusion of TDG with a sequence-specific DNA-binding domain (2012) Epigenetics, 7; Zhang, C.C., Yan, Z., Zhang, Q., Kuszpit, K., Zasadny, K., Qiu, M., Painter, C.L., VanArsdale, T., PF-03732010: a fully human monoclonal antibody against P-cadherin with antitumor and antimetastatic activity (2010) Clin. Cancer Res., 16, pp. 5177-5188
Keywords: antineoplastic activity; antineoplastic agent; Breast; breast cancer; Cancer; cancer chemotherapy; cancer model; cancer survival; drug effect; E-cadherin; Gastric; gene expression regulation; gene function; gene location; gene overexpression; gene structure; genetic association; genetic code; Helicobacter infection; Hereditary diffuse gastric cancer; human; in vivo study; loss of function mutation; lymph node metastasis; malignant neoplastic disease; molecular dynamics; molecular pathology; molecularly targeted therapy; nonhuman; P cadherin; P cadherin gene; P-cadherin; pf 03732010; priority journal; protein expression; protein function; protein inhibitor; protein processing; review; signal transduction; stomach cancer; transcription regulation; tumor gene; unclassified drug; uvomorulin; uvomorulin gene; vasculotropin inhibitor

FTIR analysis and cytotoxicity test of titanium dioxide nanoparticles - Rodrigues, L.R.; Dias, C.G.B.T.; Ceragioli, H.J.; Rodas, A.C.D.; Monteiro, F.J.M.; Zavaglia, C.A.C. (Key Engineering MaterialsKey Eng Mat, 2012)
Titanium dioxide is a material widely used in electronics industry and little explored in the biomedical area, which is the objective of this work. Nowadays one can find surgical instruments coated with thin films that have bactericidal properties when they are activated in the presence of ultraviolet light. For crystalline phase control TiO 2 was calcinated at 500°C. The crystallite mean size for sample calcinated at 500°C was 27nm. With the results of cytotoxicity it is possible to say that biomedical applications are possible. Electron microscopy images showed nanoparticles obtained by sol-gel process and the compounds were identified by FTIR analysis. Raman spectroscopy confirmed the existence of anatase titania phase and X-ray diffraction showed this material to be composed of a crystalline phase. X-ray fluorescence identified chemical contaminants. © (2012) Trans Tech Publications.
Conference code: 87411Export Date: 21 November 2012Source: ScopusCODEN: KEMAEdoi: 10.4028/www.scientific.net/KEM.493-494.768Language of Original Document: EnglishCorrespondence Address: Rodrigues, L.R.; Department of Materials Engineering, Faculty of Mechanical Engineering, State University of Campinas, Campinas, São Paulo, Brazil; email: leo5002@fem.unicamp.brReferences: Pavlova, A., Barloti, J., Teters, V., Locs, J., Berzina-Cimdina, L., (2009) Processing and Application of Ceramics, 3 (4), pp. 187-190;Naldoni, A., Minguzzi, A., Vertova, A., Santo, V.D., Borgesec, L., Bianchi, C.L., (2010) J. Mater. Chem., 21, pp. 400-407; Li, Y., Jiang, Y., Liu, F., Ren, F., Zhao, G., Leng, X., (2011) Food Hydrocolloids, 25 (5), pp. 1098-1104; Topuz, B.B., Gunduz, G., Mavis, B., Çolak, U., (2011) Dyes and Pigments, 90 (2), pp. 123-128; Nag, N., Guin, D., Basak, P., Manorama, S.V., (2008) Materials Research Bulletin, 43 (12), pp. 3270-3285; Yu, W., Qiu, J., Zhang, F., (2011) Colloids and Surfaces B: Biointerfaces, 84 (2), pp. 400-405; Wang, J., Li, S., Yan, W., Tse, S.D., Yao, Q., (2011) Proceeding of the Combustion Institute, 33 (2), pp. 1925-1932; Ma, P.X., (2008) Advanced Drug Delivery Reviews, 60, pp. 184-198; Liu, X., Smith, L.A., Hu, J., Ma, P.X., (2009) Biomaterials, 30, pp. 2252-2258; Qui, D., Yang, L., Yin, Y., Wang, A., (2011) Surface and Coatings Technology, 205 (10), pp. 3280-3284; Amin, R., Hwang, S., Park, S.H., (2011) NANO: Brief Reports and Reviews, 6 (2), pp. 101-111; Allounia, A.E., Cimpan, M.R., Hol, P.J., Skodvind, T., Gjerdet, N.R., (2009) Colloids and Surfaces B: Biointerfaces, 68, pp. 83-87; Akurati, K.K., (2008) Synthesis of TiO 2 Based Nanoparticles for Photocatalytic Applications, , 1st edition. Cuvillier Verlag Göttingen; Nag, M., Guin, D., Manorama, S.V., (2007) Materials Research Bulletin, 9, pp. 1691-1704; Birks, L.S., Friedman, H., (1946) Journal of Applied Physics, 17, pp. 687-692; Rodas, A.C.D., Maizato, M.J.S., Leiner, A.A., Pitombo, R.N.M., Polakiewicz, B., Beppu, M.M., Higa, O.Z., (2008) Artificial Organs, 32 (4), pp. 272-276; Zhang, J.Y., Boyd, I.W., O'Sullivan, B.J., Hurley, P.K., Kelly, P.V., Sénateur, J.P., (2002) Journal of Non-Crystalline Solids, 303, pp. 134-138; Arconada, N., Durán, A., Suárez, S., Portela, R., Coronado, J.M., Sánchez, B., Castro, Y., (2009) Applied Catalysis B: Environmental, 86 (1-2), pp. 1-7; Wang, J., Li, R.H., Zhang, Z.H., Sun, W., Wang, X.F., Xing, Z.Q., Xu, R., Zhang, X.D., (2008) Inorganic Materials, 44 (6), pp. 608-614; Orendorz, A., Brodyanski, A., Lösch, J., Bai, L.H., Chen, Z.H., Le, Y.K., Ziegler, C., Gnaser, H., (2007) Surface Science, 601, pp. 4390-4394
Keywords: Anatase titania; Bactericidal properties; Bioceramics; Biomedical applications; Chemical contaminants; Crystalline materials; Crystalline phase; Crystallite size; Cytotoxicity; Cytotoxicity test; Electron microscopy images; Electronics industry; FTIR; FTIR analysis; Gels; Mean size; Medical applications; nanoparticles; Nanotechnology; Oxides; Raman spectroscopy; Scherrer equation; Scherrer equations; Sol-gel process; Sol-gel with sucrose; Sol-gels; Sols; Sugar (sucrose); Surgical equipment; Surgical instrument; TiO; Titanium; Titanium dioxide; Titanium dioxide nanoparticles; Ultra-violet light; Ultraviolet radiation; X ray diffraction; X ray fluorescence

(Gd,Yb,Tb)PO 4 up-conversion nanocrystals for bimodal luminescence-MR imaging - Debasu, M.L.; Ananias, D.; Pinho, S.L.C.; Geraldes, C.F.G.C.; Carlos, L.D.; Rocha, J. (NanoscaleNanoscale, 2012)
Up-conversion (Gd,Yb,Tb)PO 4 materials and their potential for bimodal imaging have received little attention in the literature. Herein, we report the first study on the up-conversion emission of (Gd,Yb,Tb)PO 4 nanocrystals synthesized via a hydrothermal method at 150°C. These materials exhibit ultraviolet, blue and green up-conversion emissions upon excitation with a 980 nm continuous wave laser diode. The intensity of the blue-emission band at 479 nm, ascribed to the cooperative up-conversion emission of a pair of excited Yb 3+ ions, depends on the Yb 3+/Tb 3+ concentration ratio, calcination temperature and particle size. Strong green up-conversion emission of Tb 3+ is observed at 543 nm for the 5D 4 → 7F 5 transition. Relaxometry measurements reveal that the nanocrystals are efficient T 2-weighted (negative) contrast agents which, combined with visible-light emission generated by infrared excitation, affords them considerable potential for being used in bimodal, photoluminescence-magnetic resonance, imaging. © 2012 The Royal Society of Chemistry.
Keywords: Blue-emission; Calcination; Calcination temperature; Concentration ratio; Continuous wave lasers; Contrast agent; Gadolinium; Hydrothermal methods; Infrared excitation; Magnetic resonance; Magnetic resonance imaging; Nanocrystals; Relaxometry; Up-conversion; Up-conversion emission; Visible light; Ytterbium

Gradient convergence filters and a phase congruency approach for in vivo cell nuclei detection - Esteves, T.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Machine Vision and ApplicationsMach Vision Appl, 2012)
Computational methods used in microscopy cell image analysis have largely augmented the impact of imaging techniques, becoming fundamental for biological research. The understanding of cell regulation processes is very important in biology, and in particular confocal fluorescence imaging plays a relevant role for the in vivo observation of cells. However, most biology researchers still analyze cells by visual inspection alone, which is time consuming and prone to induce subjective bias. This makes automatic cell image analysis essential for large scale, objective studies of cells. While the classic approach for automatic cell analysis is to use image segmentation, for in vivo confocal fluorescence microscopy images of plants, such approach is neither trivial nor is it robust to image quality variations. To analyze plant cells in in vivo confocal fluorescence microscopy images with robustness and increased performance, we propose the use of local convergence filters (LCF). These filters are based in gradient convergence and as such can handle illumination variations, noise and low contrast.We apply a range of existing convergence filters for cell nuclei analysis of the Arabidopsis thaliana plant root tip. To further increase contrast invariance, we present an augmentation to local convergence approaches based on image phase information. Through the use of convergence index filters we improved the results for cell nuclei detection and shape estimation when compared with baseline approaches. Using phase congruency information we were able to further increase performance by 11% for nuclei detection accuracy and 4% for shape adaptation. Shape regularization was also applied, but with no significant gain, which indicates shape estimation was good for the applied filters. © 2011 Springer-Verlag.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MVAPEdoi: 10.1007/s00138-012-0407-7Language of Original Document: EnglishCorrespondence Address: Quelhas, P.; INEB-Instituto de Engenharia Biomédica, Oporto, Portugal; email: quelhas@fe.up.ptReferences: Bleau, A., Leon, L.J., Watershed-based segmentation and region merging (2000) Computer Vision and Image Understanding, 77 (3), pp. 317-370. , DOI 10.1006/cviu.1999.0822;Bresson, X., Vandergheynst, P., Thiran, J., A priori information in image segmentation: Energy functional based on shape statistical model and image information (2003) Proceedings of International Conference on Image Processing, pp. 428-428. , ICIP; Bunyak, F., Palaniappan, K., Nath, S.K., Baskin, T.I., Dong, G., Quantitative cellmotility for in vitrowound healing using level setbased active contour tracking (2011) Proceedings of the IEEE International Conference on Biomedical Imaging (ISBI), pp. 1-4; Byun, J., Verardo, M.R., Sumengen, B., Lewis, G.P., Manjunath, B.S., Fisher, S.K., Automated tool for the detection of cell nuclei in digital microscopic images: Application to retinal images (2006) Mol. Vis., 12, pp. 949-960; Campilho, A., Garcia, B., Toorn, H.V.D., Wijk, H.V., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem (2006) Plant Journal, 48 (4), pp. 619-627. , DOI 10.1111/j.1365-313X.2006.02892.x; Chan, T.F., Vese, L.A., Active contours without edges (2001) IEEE Transactions on Image Processing, 10 (2), pp. 266-277. , DOI 10.1109/83.902291; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation, classification, and tracking of cancer cell e nuclei in time-lapse microscopy (2006) IEEE Trans. Biomed. Eng., 53 (4), pp. 762-766; Chen, Y., Ladi, E., Herzmark, P., Robey, E., Roysam, B., Automated 5-d analysis of cell migration and interaction in the thymic cortex from time-lapse sequences of 3-d multi-channel multi-photon images (2009) J. Immunol. Methods, 340 (1), pp. 65-80; Chen, Y., Quelhas, P., Campilho, A., Low frame rate cell tracking: A delaunay graph matching approach (2011) Proceedings of the IEEE International Conference on Biomedical Imaging (ISBI), pp. 1-4; Clocksin, W., Automatic segmentation of overlapping nuclei with high background variation using robust estimation and flexible contour models (2003) Proceedings of the International Conference on Image Analysis and Processing, pp. 682-687; Dewitte, W., Murray, J., The plant cell cycle (2003) Annu. Rev. Plant Biol., 54, pp. 235-297; Fang, W., Chan, K.L., Incorporating shape prior into geodesic active contours for detecting partially occluded object (2007) Pattern Recognition, 40 (8), pp. 2163-2172. , DOI 10.1016/j.patcog.2006.12.014, PII S0031320306005292; Fok, Y.-L., Chan, J.C.K., Chin, R.T., Automated analysis of nerve-cell images using active contour models (1996) IEEE Transactions on Medical Imaging, 15 (3), pp. 353-368. , PII S0278006296042425; Guan, P., Yan, H., Blood cell image segmentation based on the hough transform and fuzzy curve tracing (2011) International Conference on Machine Learning and Cybernetics (ICMLC), 4, pp. 1696-1701; Hafiane, A., Bunyak, F., Palaniappan, K., Clustering initiated multiphase active contours and robust separation of nuclei groups for tissue segmentation (2008) International Conference on Pattern Recognition (ICPR), pp. 1-4; Hafiane, A., Bunyak, F., Palaniappan, K., Fuzzy clustering and active contours for histopathology image segmentation and nuclei detection (2008) Advanced Concepts for Intelligent Vision Systems LNCS, 5259, pp. 903-914. , Springer, Berlin; Han, J., Breckon, T., Randell, D., Landini, G., The application of support vector machine classification to detect cell nuclei for automated microscopy (2010) Mach. Vis. Appl., 23 (1), pp. 15-24; Harder, N., M-Bermudez, F., Godinez, W., Ellenberg, J., Eils, R., Rohr, K., Automated analysis of mitotic cell nuclei in 3d fluorescence microscopy image sequences (2008) Workshop on Bio- Image Informatics: Biological Imaging, ComputerVision AndData Mining; Hu, M., Ping, X., Ding, Y., A new active contour model and its application on cell segmentation (2004) 2004 8th International Conference on Control, Automation, Robotics and Vision (ICARCV), 2, pp. 1104-1107. , TuA7.09 - P0673, 2004 8th International Conference on Control, Automation, Robotics and Vision (ICARCV); Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Trans. Image Process., 8 (8), pp. 1029-1038; Kovesi, P., Image features from phase congruency (1999) Videre, pp. 1-26; Kovesi, P., Phase congruency detects corners and edges (2003) Digital Image Computing: Techniques and Applications, pp. 309-318; Kube, P., Properties of energy edge detectors (1992) IEEE Conference on ComputerVision and Pattern Recognition (CVPR), pp. 586-591; Leibe, B., Leonardis, A., Schiele, B., Combined object categorization and segmentation with an implicit shape model (2004) ECCV Workshop on Statistical Learning in Computer Vision, pp. 17-32; Leventon, M., Grimson, W., Faugeras, O., Statistical shape influence in geodesic active contours (2000) Proceedings of IEEE Conference on Computer Vision and Pattern Recognition (CVPR, pp. 316-323; Li, C., Xu, C., Gui, C., Fox, M.D., Level set evolution without re-initialization: A new variational formulation (2005) IEEE International Conference on Computer Vision and Pattern Recognition (CVPR), pp. 430-436; Li, K., Miller, E.D., Chen, M., Kanade, T., Weiss, L.E., Campbell, P.G., Cell population tracking and lineage construction with spatiotemporal context (2008) Med. Image Anal., 12, pp. 546-566; Lindeberg, T., Scale-space theory: A basic tool for analysing structures at different scales (1994) J. Appl. Stat., 21 (2), pp. 224-270; Marcuzzo, M., Guichard, T., Quelhas, P., Mendonça, A.M., Campilho, A., Cell division detection on the Arabidopsis thaliana root (2009) Proceedings of the Iberian Conference on Pattern Recognition and Image Analysis, LNCS, 5524, pp. 168-175. , Springer, Berlin; Marcuzzo, M., Quelhas, P., Campilho, A., Maria Mendonça, A., Campilho, A., Automated Arabidopsis plant root cell segmentation based on svm classification and region merging (2009) Comput Biol Med, 39 (9), pp. 785-793; Marcuzzo, M., Quelhas, P., Mendonça, A.M., Campilho, A., Evaluation of symmetry enhanced sliding band filter for plant cell nuclei detection in low contrast noisy fluorescent images (2009) Proceedings of the International Conference on Image Analysis and Recognition, 5627, pp. 824-831. , Springer, Berlin; Marcuzzo, M., Quelhas, P., Mendonça, A.M., Campilho, A., Tracking of Arabidopsis thaliana root cells in time-lapsemicroscopy (2009) Proceedings of the International Conference on Pattern Recognition (ICPR), pp. 1-4; Moore, P., Molloy, D., A survey of computer-based deformable models (2007) International Machine Vision and Image Processing Conference, pp. 55-66; Morrone, M., Burr, D., Feature detection in human vision: A phase-dependent energy model (1988) Proc. Roy. Soc. Lond. B Biol. Sci., 235 (1280), pp. 221-245; Mosaliganti, K., Gelas, A., Gouaillard, A., Megason, S., Microscopy image analysis: Blob segmentation using geodesic active contours (2009) Insight J.; Otsu Nobuyuki, Threshold selection method from gray-level histograms (1979) IEEE Trans Syst Man Cybern, SMC-9 (1), pp. 62-66; Pereira, C.S., Fernandes, H., Mendonça, A.M., Campilho, A.C., Detection of lung nodule candidates in chest radiographs (2007) Iberian Conference on Pattern Recognition and Image Analysis, 2, pp. 170-177; Perona Pietro, Malik Jitendra, Scale-space and edge detection using anisotropic diffusion (1990) IEEE Transactions on Pattern Analysis and Machine Intelligence, 12 (7), pp. 629-639. , DOI 10.1109/34.56205; Quelhas, P., Monay, F., Odobez, J.-M., Gatica-Perez, D., Tuytelaars, T., A thousand words in a scene (2007) IEEE Transactions on Pattern Analysis and Machine Intelligence, 29 (9), pp. 1575-1589. , DOI 10.1109/TPAMI.2007.1155; Quelhas, P., Marcuzzo, M., Oliveira, M.J., Mendonça, A.M., Campilho, A., Cancer cell detection and invasion depth estimation in brightfield images (2009) Proceedings of the British Machine Vision Conference; Quelhas, P., Marcuzzo, M., Mendonca, A.M., Campilho, A., Cell nuclei and cytoplasm joint segmentation using the sliding band filter (2010) IEEE Trans. Med. Imaging, 29 (8), pp. 1463-1473; Quelhas, P., Mendonça, A.M., Campilho, A., 3d cell nuclei fluorescence quantification using sliding band filter (2010) International Conference on Pattern Recognition (ICPR), pp. 2508-2511; Roberts, T., McKenna, S., Du, C.J., Wuyts, N., Valentine, T., Bengough, A., Estimating the motion of plant root cells from in vivo confocal laser scanning microscopy images (2010) Mach. Vis. Appl., 21, pp. 921-939; Sanz, L., Dewitte, W., Forzani, C., Patell, F., Nieuwland, J., Wen, B., Quelhas, P., Murray, J.A., The Arabidopsis d-type cyclin cycd2;1 and the inhibitor ick2/krp2 modulate auxin-induced lateral root formation (2011) Plant Cell, 23, pp. 641-660; Sivic, J., Zisserman, A., Video google: A text retrieval approach to object matching in videos (2003) Proceedings of the IEEE International Conference on Computer Vision (ICCV), pp. 1-8; Tek, F.B., Dempster, A.G., Kale, I., Blood cell segmentation using minimum area watershed and circle radon transformations (2005) Mathematical Morphology: 40 Years On, Computational Imaging and Vision, 30, pp. 441-454. , Ronse, C., Najman, L., Decencière, E. (eds.), Springer, Netherlands; Usaj, M., Torkar, D., Kanduser, M., Mikalavcic, D., Cell counting tool parameters optimization approach for electroporation efficiency determination of attached cells in phase contrast images (2011) J. Microsc., 241 (3), pp. 303-314; Vincent Luc, Soille Pierre, Watersheds in digital spaces: An efficient algorithm based on immersion simulations (1991) IEEE Transactions on Pattern Analysis and Machine Intelligence, 13 (6), pp. 583-598. , DOI 10.1109/34.87344; Wei Jun, Hagihara Yoshihiro, Kobatake Hidefumi, Detection of cancerous tumors on chest X-ray images - candidate detection filter and its evaluation (1999) IEEE International Conference on Image Processing, 3, pp. 397-401; Wei, J., Hagihara, Y., Kobatake, H., Edge detection and skeletonization using quantized localized phase (2009) European Signal Processing Conference (EUSIPCO), pp. 1542-1546; Willamowski, J., Arregui, D., Csurka, G., Dance, C.R., Fan, L., Categorizing nine visual classes using local appearance descriptors (2004) ICPR Workshop on Learning for Adaptable Visual Systems, pp. 1-11; Willemse, J., Kulikova, O., Jong, H., Bisseling, T., A new wholemount dna quantification method and the analysis of nuclear DNA content in the stem-cell niche of Arabidopsis roots (2008) Plant J., 55 (5), pp. 886-894; Xiong, G., Zhou, X., Ji, L., Automated segmentation of drosophila RNAi fluorescence cellular images using deformable models (2006) IEEE Transactions on Circuits and Systems I: Regular Papers, 53 (11), pp. 2415-2424. , DOI 10.1109/TCSI.2006.884461; Xiong, G., Zhou, X., Ji, L., Bradley, P., Perrimon, N., Wong, S., Segmentation ofDrosophila RNAI fluorescence images using level sets (2006) Proceedings of IEEE International Conference on Image Processing, pp. 73-76; Xue, Q., Degrelle, S., Wang, J., Hue, I., Guillomot, M., A level set based hybrid framework for confocal image segmentation (2008) Proceedings of the IASTED International Conference on Biomedical Engineering, pp. 453-457; Yan, P., Zhou, X., Shah, M., Wong, S.T.C., Automatic segmentation of high-throughput RNAi fluorescent cellular images (2008) IEEE Transactions on Information Technology in Biomedicine, 12 (1), pp. 109-117. , DOI 10.1109/TITB.2007.898006; Yang, X., Li, H., Zhou, X., Nuclei segmentation using marker-controlled watershed, tracking using mean-shift, and Kalman filter in time-lapse microscopy (2006) IEEE Transactions on Circuits and Systems I: Regular Papers, 53 (11), pp. 2405-2414. , DOI 10.1109/TCSI.2006.884469; Yi Wang, F.H., Jiankun, H., Fengling, H., Enhanced gradientbased algorithm for the estimation of fingerprint orientation fields Appl. Math. Comput., 185, pp. 823-833. , http://seit.unsw.adfa.edu.au/staff/sites/hu/Sample_Publication/ Elsevier_Wang.pdf; Yin, Z., Bise, R., Chen, M., Kanade, T., Cell segmentation in microscopy imagery using a bag of local Bayesian classifiers (2010) Proceedings of the IEEE International Conference on Biomedical Imaging (ISBI), pp. 125-128
Keywords: Arabidopsis thaliana; Biological research; Cell analysis; Cell images; cell nucleus; Cell regulation; Cell segmentation; Cells; Confocal fluorescence imaging; Confocal fluorescence microscopy; Convergence filters; cytology; Detection accuracy; Estimation; Fluorescence microscopy; Illumination variation; Image analysis; Image filtering; Image segmentation; Imaging techniques; In-vivo; Information use; Local Convergence; Local image filtering; Medical applications; Phase congruency; Phase information; Plant cells; Plant roots; Plants (botany); Quality variation; Shape adaptation; Shape estimation; Shape regularization; Visual inspection

Hand detection and tracking using the skeleton of the blob for medical rehabilitation applications - Gil-Jiménez, P.; Losilla-López, B.; Torres-Cueco, R.; Campilho, A.; López-Sastre, R. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
This article presents an image processing application for hand detection and tracking using the 4-connected skeleton of the segmentation mask. The system has been designed to be used with techniques of virtual reality to develop an interactive application for phantom limb pain reduction in therapeutic treatments. One of the major contributions is the design of a fast and accurate skeleton extractor, that has proven to be faster than those available in the literature. The skeleton allows the system to precisely detect the position of all the interest points of the hand (namely the fingers and the hand center). The system, composed of both the hand detector and tracker, and the virtual reality application, can work in real-time, allowing the patient to watch the virtual image of his own hand on a screen. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_16Language of Original Document: EnglishCorrespondence Address: Gil-Jiménez, P.; Universidad de Alcalá, Alcalá de Henares, Madrid, Spain; email: pedro.gil@uah.esReferences: Breuer, P., Eckes, C., Müller, S., Hand Gesture Recognition with a Novel IR Time-of-Flight Range Camera-A Pilot Study (2007) LNCS, 4418, pp. 247-260. , Gagalowicz, A., Philips, W. (eds.) MIRAGE 2007. Springer, Heidelberg;Chang, C., Lin, C., (2001) LIBSVM: A Library for Support Vector Machines, , http://www.csie.ntu.edu.tw/~cjlin/libsvm, software available at; Cole, J., Crowle, S., Austwick, G., Slater, D.H., Exploratory findings with virtual reality for phantom limb pain; from stump motion to agency and analgesia (2009) Disability and Rehabilitation, 31 (10), pp. 846-854; Elgammal, A., Muang, C., Hu, D., Skin detection - A short tutorial (2009) Encyclopedia of Biometrics; Gómez-Moreno, H., Maldonado-Bascón, S., Gil-Jiménez, P., Lafuente-Arroyo, S., (2010) Goal Evaluation of Segmentation Algorithms for Traffic Sign Recognition, 11 (4), pp. 917-930. , July; González, R., Woods, R., (1993) Digital Image Processing, , Addison-Wesley; Von Hardenberg, C., Bérard, F., Bare-hand human-computer interaction (2001) Proceedings of the 2001 Workshop on Perceptive User Interfaces, PUI 2001, pp. 1-8; Hsieh, C.C., Liou, D.H., Lee, D., A real time hand gesture recognition system using motion history image (2010) 2010 2nd International Conference on Signal Processing Systems (ICSPS), 2, pp. V2394-V2398. , July; Imai, A., Shimada, N., Shirai, Y., 3-d hand posture recognition by training contour variation (2004) Proceedings of Sixth IEEE International Conference on Automatic Face and Gesture Recognition, pp. 895-900. , May; Isaacs, J., Foo, J., Hand pose estimation for american sign language recognition (2004) Southern Symposium on System Theory, pp. 132-136; Lakshmi, J.K., Punithavalli, M., A survey on skeletons in digital image processing (2009) Digital Image Processing, pp. 260-269; Letessier, J., Bérard, F., Visual tracking of bare fingers for interactive surfaces (2004) Proceedings of the 17th Annual ACM Symposium on User Interface Software and Technology, UIST 2004, pp. 119-122. , ACM; Lewis, J.S., Kersten, P., McCabe, C.S., McPherson, K.M., Blake, D.R., Body perception disturbance: A contribution to pain in complex regional pain syndrome (2007) CRPS; McCabe, C.S., Haigh, R.C., Ring, E.F., Halligan, P.W., Wall, P.D., Blake, D.R., A controlled pilot study of the utility of mirror visual feedback in the treatment of complex regional pain syndrome (type 1) (2003) Rheumatology, 42 (1), pp. 97-101; Murray, C.D., Patchick, E., Pettifer, S., Howard, T., Caillette, F., Kulkarni, J., Bamford, C., Investigating the efficacy of a virtual mirror box in treating phantom limb pain in a sample of chronic sufferers (2006) Disabil Human Dev., 5 (3), pp. 227-234; Nope, R., Sandra, E., Humberto Loaiza, C., Eduardo Caicedo, B., Estudio omparativo de técnicas para el reconocimiento de gestos por visión artificial (2009) Avances en Sistemas e Informtica, 5 (3); Oikonomidis, I., Nikolaos, K., Argyros, A.A., Efficient model-based 3d tracking of hand articulations using kinect (2011) Tracking Hand Articulations Using Kinect; Pugeault, N., Bowden, R., Spelling it out: Real-time ASL fingerspelling recognition IEEE Workshop on Consumer Depth Cameras for Computer Vision (2011); Ren, Z., Meng, J., Yuan, J., Zhang, Z., Robust hand gesture recognition with kinect sensor (2011) Proceedings of the 19th ACM International Conference on Multimedia, MM 2011, pp. 759-760. , ACM; Yoruk, E., Konukoglu, E., Sankur, B., Darbon, J., Shape-based hand recognition (2006) IEEE Transactions on Image Processing, 15 (7), pp. 1803-1815
Keywords: blob skeleton; Hand detection; hand detection and tracking; Image analysis; Image processing applications; Interactive applications; Musculoskeletal system; phantom limb pain reduction; Therapeutic treatments; Virtual images; virtual reality

The importance of antimicrobial peptides and their potential for therapeutic use in ophthalmology - Silva, N.C.; Sarmento, B.; Pintado, M. (International Journal of Antimicrobial AgentsInt. J. Antimicrob. Agents, 2012)
The reduced effectiveness of some of the most important antibiotics owing to increasing resistance of microorganisms as well as the absence of new classes of antimicrobial agents have been concerning researchers and clinicians in recent years. Thus, the development and approval of new compounds for clinical applications is of great importance. Among these compounds, antimicrobial peptides (AMPs) appear to be excellent candidates for the development of novel antimicrobial agents. Some AMPs and antimicrobial proteins have been shown to be active against relevant pathogens in ocular infections as well as in biofilm eradication from contact lenses. Thus, they are considered promising in the prevention and management of ocular diseases. This review summarises the main classes and characteristics of AMPs and antimicrobial proteins, in particular those found in ocular structures and fluids. Some AMPs with activity against ocular pathogens and their potential as therapeutic agents to treat and prevent ocular infections are emphasised. © 2012.
Keywords: Antimicrobial peptide; Antimicrobial protein; Ocular infection; Ophthalmology

Interactions of microbicide nanoparticles with a simulated vaginal fluid - Das Neves, J.; Rocha, C.M.R.; Gonçalves, M.P.; Carrier, R.L.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Molecular PharmaceuticsMol. Pharm., 2012)
The interaction with cervicovaginal mucus presents the potential to impact the performance of drug nanocarriers. These systems must migrate through this biological fluid in order to deliver their drug payload to the underlying mucosal surface. We studied the ability of dapivirine-loaded polycaprolactone (PCL)-based nanoparticles (NPs) to interact with a simulated vaginal fluid (SVF) incorporating mucin. Different surface modifiers were used to produce NPs with either negative (poloxamer 338 NF and sodium lauryl sulfate) or positive (cetyltrimethylammonium bromide) surface charge. Studies were performed using the mucin particle method, rheological measurements, and real-time multiple particle tracking. Results showed that SVF presented rheological properties similar to those of human cervicovaginal mucus. Analysis of NP transport indicated mild interactions with mucin and low adhesive potential. In general, negatively charged NPs underwent subdiffusive transport in SVF, i.e., hindered as compared to their diffusion in water, but faster than for positively charged NPs. These differences were increased when the pH of SVF was changed from 4.2 to 7.0. Diffusivity was 50- and 172-fold lower in SVF at pH 4.2 than in water for negatively charged and positively charged NPs, respectively. At pH 7.0, this decrease was around 20- and 385-fold, respectively. The estimated times required to cross a layer of SVF were equal to or lower than 1.7 h for negatively charged NPs, while for positively charged NPs these values were equal to or higher than 7 h. Overall, our results suggest that negatively charged PCL NPs may be suitable to be used as carriers in order to deliver dapivirine and potentially other antiretroviral drugs to the cervicovaginal mucosal lining. Also, they further reinforce the importance in characterizing the interactions of nanosystems with mucus fluids or surrogates when considering mucosal drug delivery. © 2012 American Chemical Society.
Keywords: microbicides; mucin; mucoadhesion; mucosal drug delivery; particle tracking; rheology

Mesenchymal stem cell recruitment by stromal derived factor-1-delivery systems based on chitosan/poly(γ-glutamic acid) polyelectrolyte complexes - Gonçalves, R.M.; Antunes, J.C.; Barbosa, M.A. (European Cells and MaterialsEur. Cells and Mater., 2012)
Human mesenchymal stem cells (hMSCs) have an enormous potential for tissue engineering and cell-based therapies. With a potential of differentiation into multiple lineages and immune-suppression, these cells play a key role in tissue remodelling and regeneration. Here a method of hMSC recruitment is described, based on the incorporation of a chemokine in Chitosan (Ch)/ Poly(γ-glutamic acid) (γ-PGA) complexes. Ch is a nontoxic, cationic polysaccharide widely investigated. γ-PGA is a hydrophilic, non-toxic, biodegradable and negatively charged poly-amino acid. Ch and γ-PGA, being oppositely charged, can be combined through electrostatic interactions. These biocompatible structures can be used as carriers for active substances and can be easily modulated in order to control the delivery of drugs, proteins, DNA, etc. Using the layer-by-layer method, Ch and γ-PGA were assembled into polyelectrolyte multilayers films (PEMs) with thickness of 120 nm. The chemokine stromal-derived factor-1 (SDF-1) was incorporated in these complexes and was continuously released during 120 h. The method of SDF-1 incorporation is of crucial importance for polymers assembly into PEMs and for the release kinetics of this chemokine. The Ch/γ-PGA PEMs with SDF-1 were able to recruit hMSCs, increasing the cell migration up to 6 fold to a maximum of 16.2 ± 4.9 cells/mm 2. The controlled release of SDF-1 would be of great therapeutic value in the process of hMSC homing to injured tissues. This is the first study suggesting Ch/γ-PGA PEMs as SDF-1 reservoirs to recruit hMSCs, describing an efficient method of chemokine incorporation that allows a sustained released up to 5 days and that can be easily scaled-up.
Keywords: adsorption kinetics; article; artificial membrane; Biocompatible Materials; biomaterial; cell differentiation; cell migration; cell motion; Cell Movement; Cell recruitment; chemistry; Chemokine CXCL12; chitosan; controlled study; CXCL12 protein, human; cytology; drug adsorption; drug delivery system; Drug Delivery Systems; drug derivative; drug effect; ellipsometry; enzyme linked immunosorbent assay; human; human cell; human tissue; Humans; in vitro study; isotope labeling; Layer-by-layer; Membranes, Artificial; Mesenchymal stem cell; Mesenchymal Stem Cells; metabolism; methodology; poly(gamma glutamic acid); poly(gamma-glutamic acid); Poly(γ-glutamic acid); polyglutamic acid; Protein delivery; static electricity; stromal cell derived factor 1; sustained drug release

Methamphetamine mimics the neurochemical profile of aging in rats and impairs recognition memory - Melo, P.; Magalhães, A.; Alves, C.J.; Tavares, M.A.; De Sousa, L.; Summavielle, T.; Moradas-Ferreira, P. (NeuroToxicologyNeuroToxicology, 2012)
Brain neurochemistry and cognition performance are thought to decline with age. Accumulating data indicate that similar events occur after prolonged methamphetamine (MA) exposure. Using the rat as a model, the present study was designed to uncover common alteration patterns in brain neurochemistry and memory performance between aging and prolonged MA exposure. To this end, animals were treated with a chronic binge MA administration paradigm (20. mg/kg/day from postnatal day 91 to 100). Three-age control groups received isovolumetric saline treatment and were tested at the MA age-matched period, and at 12 and 20 months. We observed that both MA and aged animals presented a long, but not short, time impairment in novelty preference and an increased anxiety-like behavior. Neurochemical analysis indicated similar MA- and age-related impairments in dopamine, serotonin and metabolites in the striatum, prefrontal cortex and hippocampus. Thus, the present data illustrate that MA may be used to mimic age-related effects on neurotransmitter systems and advocate MA treatment as a feasible animal model to study neuronal processes associated with aging. © 2012 Elsevier Inc.
Keywords: Accelerated aging; Age Factors; aging; animal behavior; animal experiment; animal model; animal tissue; Animalia; Animals; anxiety; article; behavior change; Behavior, Animal; Brain; Brain Chemistry; controlled study; corpus striatum; dopamine; Exploratory Behavior; hippocampus; Hydroxyindoleacetic Acid; long term exposure; male; Memory Disorders; mental performance; Methamphetamine; Neurochemistry; neurotransmission; nonhuman; perinatal drug exposure; prefrontal cortex; priority journal; rat; Rats; Rats, Wistar; Rattus; recognition; Recognition (Psychology); Recognition memory; serotonin; sodium chloride; Time Factors

Micropatterned silica thin films with nanohydroxyapatite micro-aggregates for guided tissue regeneration - Carvalho, A.; Pelaez-Vargas, A.; Gallego-Perez, D.; Grenho, L.; Fernandes, M.H.; De Aza, A.H.; Ferraz, M.P.; Hansford, D.J.; Monteiro, F.J. (Dental MaterialsDent. Mater., 2012)
Surface modification of biomaterials has been shown to improve the biological response to dental implants. The ability to create a controlled micro-texture on the implant via additive surface modification techniques with bioactive nanohydroxyapatite (nanoHA) may positively influence guided tissue regeneration. Objective: The main goal of this study was to produce micro-fabricated SiO 2 surfaces modified with nanohydroxyapatite particles and to characterize their influence on the biological response of Human Dental-Pulp Mesenchymal Stem Cells (hDP-MSCs) and Streptococcus mutans. Materials and methods: A combined methodology of sol-gel and soft-lithography was used to produce micropatterned SiO 2 thin films with different percentages of nanoHA micro-aggregates. The surfaces were characterized by SEM/EDS, FT-IR/ATR, AFM, XPS quantitative elemental percentage and contact angle measurements. Biological characterization was performed using hDP-MSCs cultures, while Streptococcus mutans was the selected microorganism to evaluate the bacterial adhesion on the thin films. Results: Micropatterned SiO 2 surfaces with 0%, 1% and 5% of nanoHA micro-aggregates were successfully produced using a combination of sol-gel and soft-lithography. These surfaces controlled the biological response, triggering alignment and oriented proliferation of hDP-MSCs and significant differences in the adhesion of S. mutans to the different surfaces. Significance: The micropatterned surfaces exhibited biocompatible behavior that induced an oriented adhesion and proliferation of hDP-MSCs while SiO 2 presented low bacterial adhesion. These results show that the combination of sol-gel with soft-lithography is a good approach to create micropatterned surfaces with bioactive nanoparticles for guided tissue regeneration. © 2012 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Adhesion; AFM; Aggregates; Bacteria; Bacterial adhesion; Bioactive nanoparticles; Biological characterization; Biological materials; Biological response; Biomaterials; Cell culture; Contact angle; Dental prostheses; Flowcharting; FTIR/ATR; Guided tissue regeneration; Lithography; Mesenchymal stem cell; Micro patterning; Micro-texture; Microaggregates; Micropatterned; Micropatterned surface; Micropatterning; Nano-HA; Nano-hydroxyapatite; S. mutans; SEM/EDS; Silica; Silica thin films; Soft-lithography; Sol-gel; Sol-gel process; Sol-gels; Streptococcus mutans; Surface modification techniques; Surfaces; Thin films

A model for educational simulation of the evolution of uterine contractions during labor - Bastos, L.F.; van Meurs, W.; Ayres-de-Campos, D. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2012)
Electronic fetal monitoring remains an important tool in labor ward settings, providing continuous information on fetal heart rate and maternal uterine contractions. A prompt detection of abnormalities in these signals is essential for the timely resolution of situations that may put both mother and fetus at risk. Uterine contraction signals provide information that is important to evaluate the onset and progress of labor, as well as the significance of certain fetal heart rate abnormalities. We present a model for educational simulation of the spontaneous evolution of uterine contractions during labor, which combines a previously published signal generator with literature-based pre-programmed scripts for educationally relevant scenarios. This model is an essential component of a high-fidelity simulator of intrapartum emergencies, aimed to improve the competency of healthcare providers. Real and simulated tracings were presented to three independent clinical experts who judged simulated signals to be indistinguishable or negligibly different from real tracings. © 2011 Elsevier Ireland Ltd.
Keywords: article; clinical competence; computer memory; computer program; Computer simulation; Computer-Assisted Instruction; controlled study; Educational simulations; Essential component; Female; Fetal heart rate; Fetal monitoring; Health care; Health care providers; High-fidelity simulators; Humans; labor; Labor and delivery; medical education; Medical educational simulation; Models, Biological; Neonatal monitoring; Obstetric Labor Complications; Obstetrics; Pregnancy; Script-controlled simulation; signal detection; Signal generators; Simulated signals; User-Computer Interface; Uterine activities; Uterine activity; Uterine Contraction; Uterine Monitoring; uterus contraction

Neuropeptide Y Y1 receptor antagonism increases bone mass in mice - Sousa, D.M.; Baldock, P.A.; Enriquez, R.F.; Zhang, L.; Sainsbury, A.; Lamghari, M.; Herzog, H. (BoneBone, 2012)
The neuropeptide Y system has emerged as one of the major neural signalling pathways regulating bone homeostasis. Absence of Y1 receptor signalling from bone forming osteoblasts is responsible for an enhancement on bone mass in mice, suggesting that pharmacological blockade of Y1 receptors may offer a novel anabolic treatment option for improving bone mass. Here we show that oral administration of the selective Y1 receptor antagonist BIBO3304 for 8. weeks dose-dependently increases bone mass in mice. Histomorphometric analysis revealed a significant 1.5-fold increase in cancellous bone volume in the femora of mice treated with BIBO3304. Furthermore, bone microarchitecture was improved, with greater trabecular number and trabecular thickness. This increase in bone mass was associated with a significant increase in bone anabolic activity of osteoblasts and, interestingly, was evident despite a coincident increase in bone resorption, as evidenced by an increase in the number of the osteolytic osteoclasts. Changes were also evident in cortical bone, with a significant increase in periosteal mineral apposition rate. Importantly, no adverse extra-skeletal side effects were observed through Y1 receptor antagonism over the 8-week treatment period, with no effects of even the higher BIBO3304 dose on body weight, adiposity, energy metabolism or circulating corticosterone levels. Taken together, this work describes the first NPY-based anabolic treatment for improving bone mass, and highlights the therapeutic potential of blocking Y1 receptor signalling for the prevention of, or recovery from, degenerative skeletal diseases. © 2012 Elsevier Inc.
Keywords: animal experiment; animal tissue; Animals; Arginine; article; body weight; Bone Density; bone mass; bone metabolism; bone strength; cancellous bone; controlled study; cortical bone; corticosterone; corticosterone blood level; dose response; Dose-Response Relationship, Drug; drug effect; drug mechanism; drug megadose; energy metabolism; femur; food intake; glucose; glucose homeostasis; Homeostasis; male; Mice; Mice, Inbred C57BL; morphometrics; mouse; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide; neuropeptide Y; Neuropeptide yY; nonhuman; obesity; Oral drug administration; osteoblast; osteoclast activity; Osteogenesis; osteolysis; Osteopenia; Receptors, Neuropeptide Y; signal transduction; trabecular bone; Y1 receptor antagonism

A novel nanoparticle delivery system for in vivo targeting of the sciatic nerve: Impact on regeneration - Gonçalves, N.P.; Oliveira, H.; Pêgo, A.P.; Saraiva, M.J. (NanomedicineNanomedicine, 2012)
Aim: Innovative solutions in the development of drug delivery systems targeting the nerve tissue are awaited. In this regard, a novel system for the delivery of drugs to the sciatic nerve was created using nanomedical principles. Materials & methods: Chitosan was the vehicle material used in the experiment. Heparin bound to growth factors has been administered to enhance peripheral nerve regeneration, and since heparin possesses the appropriate charge to be able to form nanoparticles with chitosan, it appears to be a good candidate to base this new delivery system on. Results: Maximal absorption took place throughout the extracellular matrix at day 15. No major inflammatory response was observed, indicating that this is a safe and biocompatible system for drug delivery to nerves. Sensorimotor performance and nerve regeneration of mice receiving these nanoparticles were superior as compared with controls. Conclusion: Our work demonstrates a versatile nanoparticle delivery system that successfully targets drugs 'in vivo to the sciatic nerve, opening novel avenues in the field of nanomedicine to the design of therapeutic strategies that enhance axonal regeneration. © 2012 Future Medicine Ltd.
Keywords: chitosan; drug delivery system; heparin; nanomedicine; nanoparticles; peripheral nerve regeneration; sciatic nerve

Osteoporotic hip fractures: Bisphosphonates sales and observed turning point in trend. A population-based retrospective study - Alves, Sandra Maria; Economou, Theodoros; Oliveira, Carla; Ribeiro, Ana Isabel; Neves, Nuno; Goméz-Barrena, Enrique; de Pina, Maria de Fátima (Bone %@ 8756-3282, 2012)

Poor reliability of visual analysis of fetal heart rate tracings: What should be done about it? - Bernardes, J.; Ayres-de-Campos, D. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2012)
Keywords: accuracy; Cardiotocography; clinical decision making; clinical practice; computer analysis; fetus blood sampling; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; letter; medical education; metabolic acidosis; newborn disease; priority journal; reliability; visual acuity

Preparation and characterization of collagen-nanohydroxyapatite biocomposite scaffolds by cryogelation method for bone tissue engineering applications - Rodrigues, S.C.; Salgado, C.L.; Sahu, A.; Garcia, M.P.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2012)
Recent efforts of bone repair focus on development of porous scaffolds for cell adhesion and proliferation. Collagen-nanohydroxyapatite (HA) scaffolds (70:30; 50:50; and 30:70 mass percentage) were produced by cryogelation technique using 1-ethyl-3-(3-dimethyl aminopropyl) carbodiimide hydrochloride/N-hydroxysuccinimide as crosslinking agents. A pure collagen scaffold was used as control. Morphology analysis revealed that all cryogels had highly porous structure with interconnective porosity and the nanoHA aggregates were randomly dispersed throughout the scaffold structure. Chemical analysis showed the presence of all major peaks related to collagen and HA in the biocomposites and indicated possible interaction between nanoHA aggregates and collagen molecules. Porosity analysis revealed an enhancement in the surface area as the nanoHA percentage increased in the collagen structure. The biocomposites showed improved mechanical properties as the nanoHA content increased in the scaffold. As expected, the swelling capacity decreased with the increase of nanoHA content. In vitro studies with osteoblasts cells showed that they were able to attach and spread in all cryogels surfaces. The presence of collagen-nanoHA biocomposites resulted in higher overall cellular proliferation compared to pure collagen scaffold. A statistically significant difference between collagen and collagen-nanoHA cryogels was observed after 21 day of cell culture. These innovative collagen-nanoHA cryogels could have potentially appealing application as scaffolds for bone regeneration. © 2012 Wiley Periodicals, Inc.
Keywords: Biomaterials; Bone tissue engineering; Collagen; Cryogels; Nanohydroxyapatite

Proactive engineering - Duarte, C.; Oliveira, H.P.; Magalhaes, F.; Tavares, V.G.; Campilho, A.C.; De Oliveira, P.G. (IEEE Global Engineering Education Conference, EDUCONIEEE Global Eng. Edu. Conf., EDUCON, 2012)
This paper presents two initiatives run by groups of engineering students at the University of Porto: the Microelectronics Students' Group and BioStar. These groups are student-led initiatives that promote different scientific fields through self-guided projects. Both experiences have proven to be very successful in increasing the undergraduate student's interest in science and technology. This work reports the activities, organization and main methodologies employed by these groups, which can be seen as successful approaches to enhance the technical curriculum of students. © 2012 IEEE.
Conference code: 91215Export Date: 21 November 2012Source: ScopusArt. No.: 6201104doi: 10.1109/EDUCON.2012.6201104Language of Original Document: EnglishCorrespondence Address: Duarte, C.; INESC TEC (Formerly INESC Porto), Faculty of Engineering, University of Porto, Rua Dr. Roberto Frias, 378, 4200-465 Porto, PortugalReferences: Gheorghe, C., Covrig, M., Uncuta, S., Popescu, M., Does the implementation of the Bologna process in higher technical education require a new approach to motivate the actors involved in the educational process? (2011) 7th International Symposium on Advanced Topics in Electrical Engineering (ATEE'2011), pp. 1-4. , May;(2011) Microelectronics Students' Group, , http://usgroup.eu; (2011) BioStar, , http://biostar.fe.up.pt; Coke, P., Duarte, C., Cardoso, A., Tavares, V.G., De Oliveira, P.G., Network Infrastructure for academic IC CAD environments (2011) IEEE International Conference on Computer As A Tool (EUROCON'2011), pp. 1-4. , Apr; Clarke, P., Students win training for being Cadence's fastest' designers (2009) EE Times, , http://eetimes.eu, ID 217500055 May 14; Magalhães, F., Oliveira, H.P., Campilho, A., (2010) SPD2010-Fingerprint Singular Points Detection Competition, , http://fe.up.pt/-spd2010/; Magalhães, F., Oliveira, H.P., Matos, H., Campilho, A., (2011) HGC2011-Hand Geometric Points Detection Competition, , http://www.fe.up.pt/-hgc2011/; Duarte, C., Student group works on designs for a fully integrated wireless receiver (2009) IEEE Region 8 News, 2 (4), p. 9. , Dec; Dias, D., (2011) Computational Vision Applied to the Segmentation and Morphmetric Characterization of the Sciatic Nerve in Microscopic Images, , M.Sc. Thesis, Faculdade de Engenharia, Universidade do Porto, Jul; Martins, D., (2011) Biometric Recognition Based on the Texture Along Palmprint Principal Lines, , M.Sc. Thesis, Faculdade de Engenharia, Universidade do Porto, Jul; Matos, H., (2011) Hand Geometry Based Recognition System, , M.Sc. Thesis, Faculdade de Engenharia, Universidade do Porto, Jan; Soares, J., (2011) Uncalibrated Stereo Vision Applied to Breast Cancer Treatment Aesthetic Assessment, , M.Sc. Thesis, Faculdade de Engenharia, Universidade do Porto, Jul; Matos, H., Magalhães, F., Oliveira, H.P., Cardoso, J.S., Hand geometry based recognition system-A new method with no constraints on image acquisition (2011) Proceedings of the 4th Meeting of Young Researchers of the University of Porto; Gaspar, D., Bre, L., Bishoff, N., Domingues, I., Mammograms image processing (2011) Proceedings of the 4th Meeting of Young Researchers of the University of Porto; Magalhães, F., Oliveira, H.P., Campilho, A.C., A new method for the detection of singular points in fingerprint images (2009) Proceedings of the IEEE Workshop on Applications of Computer Vision, pp. 157-162; Moreira, I.C., Amaral, I., Domingues, I., Cardoso, A., Cardoso, M.J., Cardoso, J.S., INbreast: Toward a full-field digital mammographic database (2011) Academic Radiology; Oliveira, H.P., Magalhaes, A., Cardoso, M.J., Cardoso, J.S., An accurate and interpretable model for BCCT.core (2010) Proceedings of the 32nd Annual International Conference of the IEEE Engineering in Medicine and Biology Society, pp. 6158-6161; (2011) IJUP-Junior Reasearch at UP, , http://ijup.up.pt, University of Porto
Keywords: Curricula; Engineering education; Microelectronics; Project based learning; project-based learning; Science and Technology; Scientific fields; student-led initiatives; Students; Undergraduate students

Reciprocal induction of human dermal microvascular endothelial cells and human mesenchymal stem cells: Time-dependent profile in a co-culture system - Laranjeira, M.S.; Fernandes, M.H.; Monteiro, F.J. (Cell ProliferationCell Prolif., 2012)
Objectives: Angiogenesis is closely associated with osteogenesis where reciprocal interactions between endothelial and osteoblast cells play an important role in bone regeneration. For these reasons, the aim of this work was to develop a co-culture system to study in detail any time-dependent interactions between human mesenchymal stem cells (HMSC) and human dermal microvascular endothelial cells (HDMEC), co-cultured in a 2D system, for 35 days. Materials and methods: HMSC and HDMEC were co-cultured at a ratio of 1:4, respectively. Single-cell cultures were used as controls. Cell viability/proliferation was assessed using MTT, DNA quantification and calcein-AM assays. Cell morphology was monitored using confocal microscopy, and real time PCR was performed. Alkaline phosphatase activity and histochemical staining were evaluated. Matrix mineralization assays were also performed. Results: Cells were able to grow in characteristic patterns maintaining their viability and phenotype expression throughout culture time, compared to HMSC and HDMEC monocultures. HMSC differentiation seemed to be enhanced in the co-culture conditions, since it was observed an over expression of osteogenesis-related genes, and of ALP activity. Furthermore, presence of calcium phosphate deposits was also confirmed. Conclusions: This work reports in detail the interactions between HMSC and HDMEC in a long-term co-culture 2D system. Endothelial and mesenchymal stem cells cultured in the present co-culture conditions ensured proliferation and phenotype differentiation of cell types, osteogenesis stimulation and over-expression of angiogenesis-related genes, in the same culture system. It is believed that the present work can lead to significant developments for bone tissue regeneration and cell biology studies. © 2012 Blackwell Publishing Ltd.
Keywords: alkaline phosphatase; article; Base Sequence; calcein; calcium phosphate; CD31 antigen; Cell culture; cell differentiation; cell growth; cell interaction; cell nucleus; cell population; cell proliferation; cell structure; cell viability; coculture; Coculture Techniques; confocal microscopy; controlled study; DNA; DNA determination; DNA Primers; Endothelium, Vascular; enzyme histochemistry; F actin; flow cytometry; gene overexpression; human; human cell; Humans; immunohistochemistry; in vitro study; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Confocal; Microscopy, Electron, Scanning; microvascular endothelial cell; Microvessels; mineralization; nucleotide sequence; osteoblast; phenotype; process development; real time polymerase chain reaction; Real-Time Polymerase Chain Reaction; scanning electron microscope; single cell analysis; Skin

Regenerative medicine for the treatment of spinal cord injury: More than just promises? - Pêgo, A.P.; Kubinova, S.; Cizkova, D.; Vanicky, I.; Mar, F.M.; Sousa, M.M.; Sykova, E. (Journal of Cellular and Molecular MedicineJ. Cell. Mol. Med., 2012)
Spinal cord injury triggers a complex set of events that lead to tissue healing without the restoration of normal function due to the poor regenerative capacity of the spinal cord. Nevertheless, current knowledge about the intrinsic regenerative ability of central nervous system axons, when in a supportive environment, has made the prospect of treating spinal cord injury a reality. Among the range of strategies under investigation, cell-based therapies offer the most promising results, due to the multifactorial roles that these cells can fulfil. However, the best cell source is still a matter of debate, as are clinical issues that include the optimal cell dose as well as the timing and route of administration. In this context, the role of biomaterials is gaining importance. These can not only act as vehicles for the administered cells but also, in the case of chronic lesions, can be used to fill the permanent cyst, thus creating a more favourable and conducive environment for axonal regeneration in addition to serving as local delivery systems of therapeutic agents to improve the regenerative milieu. Some of the candidate molecules for the future are discussed in view of the knowledge derived from studying the mechanisms that facilitate the intrinsic regenerative capacity of central nervous system neurons. The future challenge for the multidisciplinary teams working in the field is to translate the knowledge acquired in basic research into effective combinatorial therapies to be applied in the clinic. © 2012 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Keywords: Biomaterials; Cell therapies; Clinical trials; Conditioning lesion; Gene therapy; Growth factors; Spinal cord injury; Stem cells

Staphylococcus aureus and Staphylococcus epidermidis adhesion to nanohydroxyapatite in the presence of model proteins - Ribeiro, M.; Monteiro, F.J.; Ferraz, M.P. (Biomedical Materials (Bristol)Biomed. Mater., 2012)
Bacterial infections can have adverse effects on the efficacy, lifetime, and safety of an implanted device. The aim of this study was to investigate the initial adhesion of several strains, namely S. aureus and S. epidermidis, on two distinct types of nanohydroxyapatite (nanoHA), sintered at 725°C and 1000°C. A comparison was also made with nanohydroxyapatite having adsorbed fetal bovine serum (FBS), human fibronectin (FN) and human serum albumin (HSA). Adhered bacterial cells were examined by scanning electron microscopy and quantified as colony forming units after being released by sonication. The wettability of the sample surface with and without adsorbed protein was assessed by contact-angle measurements. NanoHA sintered at 1000°C showed lower bacterial adhesion than this heat-treated at 725°C. Adsorption of FBS onto the nanoHA surface caused a decrease in the adhesion of all strains on both materials. The bacterial adhesion patterns in the presence of FN were different for both nanoHA substrates; the adherence of the bacterial strains, except for the clinical strain of S.epidermidis, was significantly higher on nanoHA 1000 in comparison to nanoHA 1000 without protein and the bacterial adhesion on the FN-coated nanoHA 725 was lower in comparison to the bare nanoHA 725. The effect of HSA on bacterial adhesion was concentration and bacterial strain dependent. © 2012 IOP Publishing Ltd.
Keywords: Adhesion; Adsorption; Adverse effect; article; Bacteria; Bacterial adhesion; bacterial cell; Bacterial cells; Bacterial infections; bacterial strain; Bacterial strains; bacterium adherence; Clinical strains; colony forming unit; Colony forming units; Contact angle; Contact-angle measurements; controlled study; Enzyme inhibition; Epidermidis; Fetal bovine serum; Fibronectin; heating; Human fibronectin; human serum albumin; Human serum albumins; hydroxyapatite; Implanted device; materials testing; Model proteins; Nano-HA; Nano-hydroxyapatite; Nanohydroxyapatite; nanoparticle; nonhuman; Proteins; S. aureus; Sample surface; Scanning electron microscopy; serum; Sintering; Staphylococcus aureus; Staphylococcus epidermidis; surface property; ultrasound; unclassified drug; wettability

Supervised content based image retrieval using radiology reports - Ramos, J.; Kockelkorn, T.; Van Ginneken, B.; Viergever, M.A.; Ramos, R.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2012)
Content based image retrieval (CBIR) is employed in medicine to improve radiologists' diagnostic performance. Today effective medical CBIR systems are limited to specific applications, as to reduce the amount of medical knowledge to model. Although supervised approaches could ease the incorporation of medical expertise, its application is not common due to the scarce number of available user annotations. This paper introduces the application of radiology reports to supervise CBIR systems. The concept is to make use of the textual distances between reports to build a transformation in image space through a manifold learning algorithm. A comparison was made between the presented approach and non-supervised CBIR systems, using a Leave-One-Patient-Out evaluation in a database of computer tomography scans of interstitial lung diseases. Supervised CBIR augmented the mean average precision consistently with an increase between 3 to 8 points, which suggests supervision by radiology reports increases CBIR performance. © 2012 Springer-Verlag.
Conference code: 91199Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-31298-4_30Language of Original Document: EnglishCorrespondence Address: Ramos, J.; INEB - Instituto de Engenharia Biomédica, Faculdade de Engenharia, Universidade Do PortoPortugalReferences: Aisen, A.M., Broderick, L.S., Winer-Muram, H., Brodley, C.E., Kak, A.C., Pavlopoulou, C., Dy, J., Marchiori, A., Automated storage and retrieval of thin-section CT images to assist diagnosis: System description and preliminary assessment (2003) Radiology, 228 (1), pp. 265-270;Akgul, C.B., Rubin, D.L., Napel, S., Beaulieu, C.F., Greenspan, H., Acar, B., Content-Based image retrieval in radiology: Current status and future directions (2010) Journal of Digital Imaging, 24 (2), pp. 208-222; Dreyer, K.J., Kalra, M.K., Maher, M.M., Hurier, A.M., Asfaw, B.A., Schultz, T., Halpern, E.F., Thrall, J.H., Application of recently developed computer algorithm for automatic classification of unstructured radiology reports: Validation study1 (2005) Radiology, 234 (2), pp. 323-329; Hersh, W.R., Mülller, H., Jensen, J.R., Yang, J., Gorman, P.N., Ruch, P., Advancing biomedical image retrieval: Development and analysis of a test collection (2006) Journal of the American Medical Informatics Association: JAMIA, 13 (5), pp. 488-496; Kelly, D., Teevan, J., Implicit feedback for inferring user preference: A bibliography (2003) SIGIR Forum, 37 (2), pp. 18-28; Kockelkorn, T.T.J.P., De Jong, P.A., Gietema, H.A., Grutters, J.C., Prokop, M., Van Ginneken, B., Interactive annotation of textures in thoracic CT scans (2010) Proceedings of SPIE, 7624 (1), pp. 76240X-76240X-8. , March; Li, Q., Li, F., Shiraishi, J., Katsuragawa, S., Sone, S., Doi, K., Investigation of new psychophysical measures for evaluation of similar images on thoracic computed tomography for distinction between benign and malignant nodules (2003) Medical Physics, 30 (10), pp. 2584-2593; Van Rikxoort, E.M., De Hoop, B., Van De Vorst, S., Prokop, M., Van Ginneken, B., Automatic segmentation of pulmonary segments from volumetric chest CT scans (2009) IEEE Transactions on Medical Imaging, 28 (4), pp. 621-630; Sammon, J.W., A nonlinear mapping for data structure analysis (1969) IEEE Transactions on Computers, C-18 (5), pp. 401-409; Slaney, M., Weinberger, K., White, W., Learning a metric for music similarity (2008) Procedings of the 9th International Society for Music Information Retrieval Conference, pp. 313-318; Sluimer, I.C., Prokop, M., Hartmann, I., Van Ginneken, B., Automated classification of hyperlucency, fibrosis, ground glass, solid, and focal lesions in high-resolution CT of the lung (2006) Medical Physics, 33 (7), p. 2610; Yang, L., Jin, R., Mummert, L., Sukthankar, R., Goode, A., Zheng, B., Hoi, S.C., Satyanarayanan, M., A boosting framework for Visuality-Preserving distance metric learning and its application to medical image retrieval (2010) IEEE Transactions on Pattern Analysis and Machine Intelligence, 32 (1), pp. 30-44
Keywords: CBIR system; Computer tomography; Content based retrieval; Content-Based Image Retrieval; Diagnostic performance; Image analysis; Image space; Interstitial lung disease; Learning algorithms; Manifold learning algorithm; Medical computing; Medical knowledge; Radiation; Radiology; Radiology reports; User annotations

Synthesis of an O-alkynyl-chitosan and its chemoselective conjugation with a PEG-like amino-azide through click chemistry - Oliveira, J.R.; Martins, M.C.L.; Mafra, L.; Gomes, P. (Carbohydrate PolymersCarbohydr Polym, 2012)
N-Phthaloyl-chitosan O-prop-2-ynyl carbamate was prepared as a biopolymer amenable to undergo chemoselective conjugation by azide-alkyne coupling, while allowing upturn of chitosan's amines after dephthaloylation. N-phthaloylchitosan was prepared according to previously described methods and, due to its low solubility in current organic media, subsequent modifications were run in heterogeneous conditions. Activation of hydroxyls with carbonyl-1,1′- diimidazole and coupling to propargylamine yielded N-phthaloyl-chitosan O-prop-2-ynyl carbamate, then coupled to a model PEG-like azide by azide-alkyne coupling, giving the expected triazolyl conjugate. N-Dephthaloylation allowed recovery of the free amines, responsible for chitosan's bioadhesion and tissue-regeneration properties. The structures of all polymers were confirmed by Fourier-transformed infra-red (FT-IR) and X-ray photoelectron (XPS) spectroscopies, as well as by solid-state nuclear magnetic resonance (SSNMR). All chitosan derivatives were poorly soluble in both aqueous and organic media, which makes them suitable for topical applications or for removal of toxic substances from either the gastric intestinal tract or environmental sources. © 2011 Elsevier Ltd. All Rights Reserved.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: CAPODdoi: 10.1016/j.carbpol.2011.07.043Language of Original Document: EnglishCorrespondence Address: Gomes, P.; CIQ-UP, Departamento de Química e Bioquímica, Universidade Do Porto, Rua do Campo Alegre 687, 4169-007 Porto, Portugal; email: pgomes@fc.up.ptReferences: Amaral, I.F., Granja, P., Barbosa, M.A., Chemical modification of chitosan by phosphorylation: An XPS, FT-IR and SEM study (2005) Journal of Biomaterials Science, Polymer Edition, 16, pp. 1575-1593;Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cell osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation (2005) Journal of Biomedical Materials Research, 75 A, pp. 387-397; Anitha, A., Deepa, N., Chennazhi, K.P., Nair, S.V., Tamura, H., Jayakumar, R., Development of muchoadhesive, thiolated chitosan nanoparticles for biomedical applications (2011) Carbohydrate Polymers, 83, pp. 66-73; Batista, M.K.S., Gallemí, M., Adeva, A., Gomes, C.A.R., Gomes, P., Facile regioselective synthesis of a novel chitosan-pexiganan conjugate with potential interest for the treatment of infected skin lesions (2009) Synthetic Communications, 39, pp. 1228-1240; Batista, M.K.S., Pinto, L.F., Gomes, C.A.R., Gomes, P., Novel highly-soluble peptide-chitosan polymers: Synthesis and spectral characterization (2006) Carbohydrate Polymers, 64, pp. 299-305; Beamson, G., Briggs, D., (1992) High Resolution XPS of Organic Polymers: The Scientia ESCA300 Database, , John Wiley & Sons New York (USA); Bennett, A.E., Rienstra, C.M., Auger, M., Lakshmi, K.V., Griffin, R.G., Heteronuclear decoupling in rotating solids (1995) The Journal of Chemical Physics, 103, pp. 6951-6958; Berger, J., Reist, M., Mayer, J.M., Felt, O., Gurny, R., Structure and interactions in chitosan hydrogels formed by complexation or aggregation for biomedical applications (2004) European Journal of Pharmaceutics and Biopharmaceutics, 57, pp. 35-52; Berger, J., Reist, M., Mayer, J.M., Felt, O., Peppas, N.A., Gurny, R., Structure and interactions in covalently and ionically crosslinked chitosan hydrogels for biomedical applications (2004) European Journal of Pharmaceutics and Biopharmaceutics, 57, pp. 19-34; Bhatnagar, A., Sillanpää, M., Applications of chitin- and chitosan-derivatives for the detoxification of water and wastewater: A short review (2009) Advances in Colloid and Interface Science, 152, pp. 26-38; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Argüelles-Monal, W., Desbrires, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Cabrera, J.C., Van Cutsem, P., Preparation of chitooligosaccharides with degree of polymerization higher than 6 by acid or enzymatic degradation of chitosan (2005) Biochemical Engineering Journal, 25, pp. 165-172; Chinchilla, R., Nájera, C., The Sonogashira reaction: A booming methodology in synthetic organic chemistry (2007) Chemical Reviews, 107, pp. 874-922; Chirachanchai, S., Lertworasirikul, A., Tachaboonyakiat, W., Carbaryl insecticide conjugation onto chitosan via iodochitosan and chitosan carbonyl imidazolide precursors (2001) Carbohydrate Polymers, 46, pp. 19-27; Crompton, K.E., Goud, J.D., Bellamkonda, R.V., Gengenbach, T.R., Finkelstein, D.I., Horne, M.K., Polylysine-functionalised thermoresponsive chitosan hydrogel for neural tissue engineering (2007) Biomaterials, 28, pp. 441-449; Dai, T., Tegos, G.P., Burkatovskaya, M., Castano, A.P., Hamblin, M.R., Chitosan acetate bandage as a topical antimicrobial dressing for infected burns (2009) Antimicrobial Agents and Chemotherapy, 53, pp. 393-400; Elkholy, S.S., Khalil, K.D., Elsabee, M.Z., Grafting of acryloyl cyanoacetohydrazide onto chitosan (2011) Journal of Polymer Research, 18, pp. 459-467; Gomes, P., Gomes, C.A.R., Batista, M.K.S., Pinto, L.F., Silva, P.A.P., Synthesis, structural characterization and properties of water-soluble N-(γ-propanoyl-amino acid)-chitosans (2008) Carbohydrate Polymers, 71, pp. 54-65; Holappa, J., Hjálmarsdóttir, M., Másson, M., Rúnarsson, Ö., Asplund, T., Soininen, P., Antimicrobial activity of chitosan N-betainates (2006) Carbohydrate Polymers, 65, pp. 114-118; Holappa, J., Nevalainen, T., Soininen, P., Másson, M., Järvinen, T., Synthesis of novel quaternary chitosan derivatives via N-chloroacyl-6-O-triphenylmethylchitosans (2006) Biomacromolecules, 7, pp. 407-410; Iqbal, J., Sarti, F., Perera, G., Bernkop-Schnürch, A., Development and in vivo evaluation of an oral drug delivery system for paclitaxel (2011) Biomaterials, 32, pp. 170-175; Kolb, H.C., Finn, M.G., Sharpless, K.B., Click Chemistry: Diverse chemical function from a few good reactions (2001) Angewandte Chemie International Edition, 40, pp. 2004-2021; Krishnakumar, V., John Xavier, R., FT Raman and FT-IR spectral studies of 3-mercapto-1,2,4-triazole (2004) Spectrochimica Acta - Part A: Molecular and Biomolecular Spectroscopy, 60, pp. 709-714; Kulbokaite, R., Ciuta, G., Netopilik, M., Makuska, R., N-PEGylation of chitosan via click reactions (2009) Reactive and Functional Polymers., 69, pp. 771-778; Kurita, K., Ikeda, H., Yoshida, Y., Shimojoh, M., Harata, M., Chemoselective protection of the amino groups of chitosan by controlled phthaloylation: Facile preparation of a precursor useful for chemical modifications (2002) Biomacromolecules, 3, pp. 1-4; Kurita, K., Yoshida, Y., Umemura, T., Finely selective protections and deprotections of multifunctional chitin and chitosan to synthesize key intermediates for regioselective chemical modifications (2010) Carbohydrate Polymers, 81, pp. 434-440; Lahann, J., (2009) Click Chemistry for Biotechnology and Materials Science, , John Wiley & Sons Chichester (UK); Lallana, E., Fernández-Megía, E., Riguera, R., Surpassing the use of copper in the click functionalization of polymeric nanostructures: A strain promoted approach (2009) Journal of the American Chemical Society., 131, pp. 5748-5750; Li, X., Yuan, W., Gu, S., Re, J., Synthesis and self-assembly of tunable thermosensitive chitosan amphiphilic copolymers by click chemistry (2010) Materials Letters, 64, pp. 2663-2666; Makuška, R., Gorochovceva, N., Regioselective grafting of poly(ethylene glycol) onto chitosan through C-6 position of glucosamine units (2006) Carbohydrate Polymers, 64, pp. 319-327; Meldal, M., Tomøe, C.W., Cu-catalyzed azide-alkyne cycloaddition (2008) Chemical Reviews, 108, pp. 2952-3015; Molnár, E., Barbu, E., Lien, C.-F., Górecki, D.C., Tsibouklis, J., Toward drug delivery into the brain: Synthesis, characterization, and preliminary in vitro assessment of alkylglyceryl-functionalized chitosan nanoparticles (2010) Biomacromolecules, 11, pp. 2880-2889; Montalbetti, C.A.G.N., Falque, V., Amide bond formation and peptide coupling (2005) Tetrahedron, 61, pp. 10827-10852; Muzzarelli, R.A.A., Carboxymethylated chitins and chitosans (1988) Carbohydrate Polymers, 8, pp. 1-21; Muzzarelli, R.A.A., Chitins and chitosans for the repair of wounded skin, nerve, cartilage and bone (2009) Carbohydrate Polymers, 76, pp. 167-182; Muzarelli, R.A.A., Chitosan composites with inorganics, morphogenetic proteins and stem cells, for bone regeneration (2011) Carbohydrate Polymers, 83, pp. 1433-1445; Oh, J.K., Lee, D.I., Park, J.M., Biopolymer-based microgels/nanogels for drug delivery applications (2009) Progress in Polymer Science, 34, pp. 1261-1282; Önal, S., Telefoncu, A., Comparison of chitin and amberlite IRA-938 for a-galactosidase immobilization (2003) Artifical Cells, Blood Substitutes, and Biotechnology, 31, pp. 19-33; Özba-Turan, S., Akbua, J., Sezer, A.D., Topical application of antisense oligonucleotide-loaded chitosan nanoparticles to rats (2010) Oligonucleotides, 20, pp. 147-153; Park, S.O., Kwon, O.S., Choi, C.W., Kim, C.-J., Glucosamine-mediated detoxification of p-benzoquinone and its removal by chitosan (2000) Biotechnology Letters, 22, pp. 21-24; Prabuh, K., Sundaramoorthi, V., Selvaraju, C.K., Tamilselvi, K.K.N., Topical immunization and the use of chitosan as carrier (2011) International Journal of Research in Ayurveda and Pharmacy, 2, pp. 90-94; Shen, X., Ji, Y., Yang, Q., Zheng, X., Preparation, characterization, and rheological properties of dibutyrylchitin (2007) Journal of Macromolecular Science B, 49, pp. 250-258; Socrates, G., (2001) Infrared and Raman Characteristic Group Frequencies Tables and Charts, , 3rd edition John Wiley & Sons, Ltd New York (USA); Rúnarsson, Ö., Holappa, J., Jónsdóttir, S., Steinsson, H., Másson, M., N-selective 'one-pot' synthesis of highly substituted trimethyl chitosan (TMC) (2008) Carbohydrate Polymers, 74, pp. 740-744; Rúnarsson, Ö., Holappa, J., Malainer, C., Steinsson, H., Hjálmarsdóttir, M., Nevalainen, T., Antibacterial activity of N-quaternary chitosan derivatives: Synthesis, characterization and structure activity relationship (SAR) investigations (2010) European Polymer Journal, 46, pp. 1251-1267; Wan, A., Gao, Q., Li, H., Effects of molecular weight and degree of acetylation on the release of nitric oxide from chitosan-nitric oxide adducts (2010) Journal of Applied Polymer Science, 117, pp. 2183-2188; Yuan, W., Li, X., Gu, S., Cao, A., Ren, J., Amphiphilic chitosan graft copolymer via combination of ROP, ATRP and click chemistry: Synthesis, self-assembly, thermosensitivity, fluorescence, and controlled drug release (2011) Polymer, 52, pp. 658-666; Yuan, W., Zhao, Z., Gu, S., Ren, J., Synthesis, characterization, and properties of amphiphilic chitosan copolymers with mixed side chains by click chemistry (2010) Journal of Polymer Science A, 48, pp. 3476-3486; Yuan, W., Zhao, Z., Gu, S., Ren, T., Ren, J., Synthesis and self-assembly of pH-responsive chitosan graft copolymer by the combination of atom transfer radical polymerization and click chemistry (2011) Materials Letters, 65, pp. 793-796; Zhang, J., Li, C., Xue, Z.-Y., Cheng, H.-W., Huang, F.-W., Zhuo, R.-X., Fabrication of lactobionic-loaded chitosan microcapsules as potential drug carriers targeting the liver (2011) Acta Biomaterialia, 7, pp. 1665-1673
Keywords: 1 ,3-Dipolarcycloaddition; Acetylene; Amines; Azide-alkyne coupling; Bio-adhesion; Bioadhesion; Biomaterials; chitosan; click chemistry; Cycloaddition; FTIR; Huisgen's 1,3-dipolar cycloaddition; Nuclear magnetic resonance; Nuclear magnetic resonance spectroscopy; Photoelectron spectroscopy; Resonance; Size exclusion chromatography; Size-exclusion chromatography; Solid state NMR; Solid-state NMR; Tissue; X ray photoelectron spectroscopy; XPS

Tumor cell-educated periprostatic adipose tissue acquires an aggressive cancer-promoting secretory profile - Ribeiro, R.J.T.; Monteiro, C.P.D.; Cunha, V.F.P.M.; Azevedo, A.S.M.; Oliveira, M.J.; Monteiro, R.; Fraga, A.M.; Príncipe, P.; Lobato, C.; Lobo, F.; Morais, A.; Silva, V.; et al. (Cellular Physiology and BiochemistryCell. Physiol. Biochem., 2012)
Background/Aims: The microenvironment produces important factors that are crucial to prostate cancer (PCa) progression. However, the extent to which the cancer cells stimulate periprostatic adipose tissue (PPAT) to produce these proteins is largely unknown. Our purpose was to determine whether PCa cell-derived factors influence PPAT metabolic activity. Methods: Primary cultures of human PPAT samples from PCa patients (adipose tissue organotypic explants and primary stromal vascular fraction, SVF) were stimulated with conditioned medium (CM) collected from prostate carcinoma (PC3) cells. Cultures without CM were used as control. We used multiplex analysis and ELISA for protein quantification, qPCR to determine mitochondrial DNA (mtDNA) copy number and zymography for matrix metalloproteinase activity, in order to evaluate the response of adipose tissue explants and SVFs to PC3 CM. Results: Stimulation of PPAT explants with PCa PC3 CM induced adipokines associated with cancer progression (osteopontin, tumoral necrosis factor alpha and interleukin-6) and reduced the expression of the protective adipokine adiponectin. Notably, osteopontin protein expression was 13-fold upregulated. Matrix metalloproteinase 9 activity and mitochondrial DNA copy number were higher after stimulation with cancer CM. Stromovascular cells from PPAT in culture were not influenced by tumor-derived factors. Conclusion: The modulation of adipokine expression by tumor CM indicates the pervasive extent to which tumor cells command PPAT to produce factors favorable to their aggressiveness. © 2012 S. Karger AG, Basel.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: CEPBEdoi: 10.1159/000337604PubMed ID: 22415092Language of Original Document: EnglishCorrespondence Address: Ribeiro, R.J.T.; Portuguese Institute of Oncology, Porto Centre Molecular Oncology Group -CI, Edifício Laboratórios -Piso 4, Rua Dr. António Bernardino Almeida, 4200-072 Porto, Portugal; email: oriebir.r@gmail.comChemicals/CAS: adiponectin, 283182-39-8; gelatinase B, 146480-36-6; osteopontin, 106441-73-0; Adiponectin; Culture Media, Conditioned; Cytokines; DNA, Mitochondrial; Interleukin-6; Matrix Metalloproteinase 2, 3.4.24.24; Matrix Metalloproteinase 9, 3.4.24.35; Osteopontin, 106441-73-0; Tumor Necrosis Factor-alphaReferences: Hsing, A.W., Sakoda, L.C., Chua Jr., S., Obesity, metabolic syndrome, and prostate cancer (2007) Am J Clin Nutr, 86, pp. s843-857;Cao, Y., Ma, J., Body mass index, prostate cancer-specific mortality, and biochemical recurrence: A systematic review and meta-analysis (2011) Cancer Prev Res (Phila), 4, pp. 486-501; Baillargeon, J., Rose, D.P., Obesity, adipokines, and prostate cancer (review) (2006) Int J Oncol, 28, pp. 737-745; Mistry, T., Digby, J.E., Desai, K.M., Randeva, H.S., Obesity and Prostate Cancer: A Role for Adipokines (2007) European Urology, 52 (1), pp. 46-53. , DOI 10.1016/j.eururo.2007.03.054, PII S0302283807004307; Hirano, T., Morii, H., Nakazawa, K., Murakami, D., Yamashita, A., Asahi, J., Orimo, H., Tokura, Y., Enhancement of adipogenesis induction by conditioned media obtained from cancer cells (2008) Cancer Lett, 268, pp. 286-294; Andarawewa, K.L., Motrescu, E.R., Chenard, M.-P., Gansmuller, A., Stoll, I., Tomasetto, C., Rio, M.-C., Stromelysin-3 is a potent negative regulator of adipogenesis participating to cancer cell-adipocyte interaction/crosstalk at the tumor invasive front (2005) Cancer Research, 65 (23), pp. 10862-10871. , DOI 10.1158/0008-5472.CAN-05-1231; Jotzu, C., Alt, E., Welte, G., Li, J., Hennessy, B.T., Devarajan, E., Krishnappa, S., Song, Y.H., Adipose tissue derived stem cells differentiate into carcinoma-associated fibroblast-like cells under the influence of tumor derived factors (2011) Cell Oncol (Dordr), 34, pp. 55-67; Dolinkova, M., Dostalova, I., Lacinova, Z., Michalsky, D., Haluzikova, D., Mraz, M., The endocrine profile of subcutaneous and visceral adipose tissue of obese patients (2008) Mol Cell Endocrinol, 291, pp. 63-70; Van Roermund, J.G., Hinnen, K.A., Tolman, C.J., Bol, G.H., Witjes, J.A., Bosch, J.L., Kiemeney, L.A., Van Vulpen, M., Periprostatic fat correlates with tumour aggressiveness in prostate cancer patients (2011) BJU Int, 107, pp. 1775-1779; Sumitomo, M., Asakuma, J., Yoshii, H., Sato, A., Horiguchi, A., Ito, K., Nagakura, K., Asano, T., Anterior perirectal fat tissue thickness is a strong predictor of recurrence after high-intensity focused ultrasound for prostate cancer (2010) Int J Urol, 17, pp. 776-782; Finley, D.S., Calvert, V.S., Inokuchi, J., Lau, A., Narula, N., Petricoin, E.F., Zaldivar, F., Ornstein, D.K., Periprostatic adipose tissue as a modulator of prostate cancer aggressiveness (2009) J Urol, 182, pp. 1621-1627; Thalmann, S., Juge-Aubry, C.E., Meier, C.A., Explant cultures of white adipose tissue (2008) Methods Mol Biol, 456, pp. 195-199; Song, G.J., Lewis, V., Mitochondrial DNA integrity and copy number in sperm from infertile men (2008) Fertil Steril, 90, pp. 2238-2244; Park, J., Euhus, D.M., Scherer, P.E., Paracrine and Endocrine Effects of Adipose Tissue on Cancer Development and Progression (2011) Endocr Rev, 32, pp. 550-570; George, D.J., Halabi, S., Shepard, T.F., Sanford, B., Vogelzang, N.J., Small, E.J., Kantoff, P.W., The prognostic significance of plasma interleukin-6 levels in patients with metastatic hormone-refractory prostate cancer: Results from cancer and leukemia group B 9480 (2005) Clinical Cancer Research, 11 (5), pp. 1815-1820. , DOI 10.1158/1078-0432.CCR-04-1560; Michalaki, V., Syrigos, K., Charles, P., Waxman, J., Serum levels of IL-6 and TNF-α correlate with clinicopathological features and patient survival in patients with prostate cancer (2004) British Journal of Cancer, 90 (12), pp. 2312-2316; Dirat, B., Bochet, L., Dabek, M., Daviaud, D., Dauvillier, S., Majed, B., Wang, Y.Y., Muller, C., Cancerassociated adipocytes exhibit an activated phenotype and contribute to breast cancer invasion (2011) Cancer Res, 71, pp. 2455-2465; Culig, Z., New insights into the role of interleukin-6 in human prostate cancer (2009) J Urol, 182, pp. 1255-1256; Chun, J.Y., Nadiminty, N., Dutt, S., Lou, W., Yang, J.C., Kung, H.J., Evans, C.P., Gao, A.C., Interleukin-6 regulates androgen synthesis in prostate cancer cells (2009) Clin Cancer Res, 15, pp. 4815-4822; Weber, G.F., Lett, G.S., Haubein, N.C., Osteopontin is a marker for cancer aggressiveness and patient survival (2010) Br J Cancer, 103, pp. 861-869; Thalmann, G.N., Sikes, R.A., Devoll, R.E., Kiefer, J.A., Markwalder, R., Klima, I., Farach-Carson, C.M., Chung, L.W.K., Osteopontin: Possible role in prostate cancer progression (1999) Clinical Cancer Research, 5 (8), pp. 2271-2277; McAllister, S.S., Gifford, A.M., Greiner, A.L., Kelleher, S.P., Saelzler, M.P., Ince, T.A., Reinhardt, F., Weinberg, R.A., Systemic Endocrine Instigation of Indolent Tumor Growth Requires Osteopontin (2008) Cell, 133 (6), pp. 994-1005. , DOI 10.1016/j.cell.2008.04.045, PII S0092867408006211; Balkwill, F., TNF-alpha in promotion and progression of cancer (2006) Cancer Metastasis Rev, 25, pp. 409-416; Yan, B., Wang, H., Rabbani, Z.N., Zhao, Y., Li, W., Yuan, Y., Li, F., Li, C.-Y., Tumor necrosis factor-α is a potent endogenous mutagen that promotes cellular transformation (2006) Cancer Research, 66 (24), pp. 11565-11570. , DOI 10.1158/0008-5472.CAN-06-2540; Bates, R.C., Mercurio, A.M., Tumor necrosis factor-α stimulates the epithelial-tomesenchymal transition of human colonic organoids (2003) Molecular Biology of the Cell, 14 (5), pp. 1790-1800. , DOI 10.1091/mbc.E02-09-0583; Yamauchi, T., Kamon, J., Waki, H., Terauchi, Y., Kubota, N., Hara, K., Mori, Y., Kadowaki, T., The fat-derived hormone adiponectin reverses insulin resistance associated with both lipoatrophy and obesity (2001) Nature Medicine, 7 (8), pp. 941-946. , DOI 10.1038/90984; Li, H., Stampfer, M.J., Mucci, L., Rifai, N., Qiu, W., Kurth, T., Ma, J., A 25-year prospective study of plasma adiponectin and leptin concentrations and prostate cancer risk and survival (2010) Clin Chem, 56, pp. 34-43; Ribeiro, R., Lopes, C., Medeiros, R., The link between obesity and prostate cancer: The leptin pathway and therapeutic perspectives (2006) Prostate Cancer and Prostatic Diseases, 9 (1), pp. 19-24. , DOI 10.1038/sj.pcan.4500844, PII 4500844; Vaday, G.G., Peehl, D.M., Kadam, P.A., Lawrence, D.M., Expression of CCL5 (RANTES) and CCR5 in prostate cancer (2006) Prostate, 66 (2), pp. 124-134. , DOI 10.1002/pros.20306; Kessenbrock, K., Plaks, V., Werb, Z., Matrix metalloproteinases: Regulators of the tumor microenvironment (2010) Cell, 141, pp. 52-67; Bouloumie, A., Sengenes, C., Portolan, G., Galitzky, J., Lafontan, M., Adipocyte Produces Matrix Metalloproteinases 2 and 9 Involvement in Adipose Differentiation (2001) Diabetes, 50 (9), pp. 2080-2086; Bergers, G., Brekken, R., McMahon, G., Vu, T.H., Itoh, T., Tamaki, K., Tanzawa, K., Hanahan, D., Matrix metalloproteinase-9 triggers the angiogenic switch during carcinogenesis (2000) Nat Cell Biol, 2, pp. 737-744; Lin, C.Y., Tsai, P.H., Kandaswami, C.C., Lee, P.P., Huang, C.J., Hwang, J.J., Lee, M.T., Matrix metalloproteinase-9 cooperates with transcription factor Snail to induce epithelial-mesenchymal transition (2011) Cancer Sci, 102, pp. 815-827; Chakrabarti, S., Patel, K.D., Matrix metalloproteinase-2 (MMP-2) and MMP-9 in pulmonary pathology (2005) Experimental Lung Research, 31 (6), pp. 599-621. , DOI 10.1080/019021490944232; Sehgal, G., Hua, J., Bernhard, E.J., Sehgal, I., Thompson, T.C., Muschel, R.J., Requirement for matrix metalloproteinase-9 (Gelatinase B) expression in metastasis by murine prostate carcinoma (1998) American Journal of Pathology, 152 (2), pp. 591-596; Johnson, T.R., Koul, S., Kumar, B., Khandrika, L., Venezia, S., Maroni, P.D., Meacham, R.B., Koul, H.K., Loss of PDEF, a prostatederived Ets factor is associated with aggressive phenotype of prostate cancer: Regulation of MMP 9 by PDEF (2010) Mol Cancer, 9, p. 148; Trudel, D., Fradet, Y., Meyer, F., Tetu, B., Matrix metalloproteinase 9 is associated with Gleason score in prostate cancer but not with prognosis (2010) Hum Pathol, 41, pp. 1694-1701; Zhang, L., Shi, J., Feng, J., Klocker, H., Lee, C., Zhang, J., Type IV collagenase (matrix metalloproteinase-2 and -9) in prostate cancer (2004) Prostate Cancer and Prostatic Diseases, 7 (4), pp. 327-332. , DOI 10.1038/sj.pcan.4500750, PII 4500750; Zhong, W.D., Han, Z.D., He, H.C., Bi, X.C., Dai, Q.S., Zhu, G., Ye, Y.K., Chen, Z.N., CD147, MMP-1, MMP-2 and MMP-9 protein expression as significant prognostic factors in human prostate cancer (2008) Oncology, 75, pp. 230-236; Sauer, C.G., Kappeler, A., Spath, M., Kaden, J.J., Michel, M.S., Mayer, D., Bleyl, U., Grobholz, R., Expression and activity of matrix metalloproteinases-2 and -9 in serum, core needle biopsies and tissue specimens of prostate cancer patients (2004) Virchows Archiv, 444 (6), pp. 518-526; Opdenakker, G., Masure, S., Grillet, B., Van Damme, J., Cytokine-mediated regulation of human leukocyte gelatinases and role in arthritis (1991) Lymphokine Cytokine Res, 10, pp. 317-324; Unal, R., Yao-Borengasser, A., Varma, V., Rasouli, N., Labbate, C., Kern, P.A., Ranganathan, G., Matrix metalloproteinase-9 is increased in obese subjects and decreases in response to pioglitazone (2010) J Clin Endocrinol Metab, 95, pp. 2993-3001; Catalan, V., Gomez-Ambrosi, J., Rodriguez, A., Ramirez, B., Silva, C., Rotellar, F., Gil, M.J., Frühbeck, G., Increased adipose tissue expression of lipocalin-2 in obesity is related to inflammation and matrix metalloproteinase-2 and metalloproteinase-9 activities in humans (2009) J Mol Med (Berl), 87, pp. 803-813; Villarroya, J., Giralt, M., Villarroya, F., Mitochondrial DNA: An up-and-coming actor in white adipose tissue pathophysiology (2009) Obesity (Silver Spring), 17, pp. 1814-1820; Robin, E.D., Wong, R., Mitochondrial DNA molecules and virtual number of mitochondria per cell in mammalian cells (1988) J Cell Physiol, 136, pp. 507-513; Kaaman, M., Sparks, L.M., Van Harmelen, V., Smith, S.R., Sjolin, E., Dahlman, I., Arner, P., Strong association between mitochondrial DNA copy number and lipogenesis in human white adipose tissue (2007) Diabetologia, 50 (12), pp. 2526-2533. , DOI 10.1007/s00125-007-0818-6; Yamauchi, T., Kamon, J., Waki, H., Murakami, K., Motojima, K., Komeda, K., Ide, T., Kadowaki, T., The mechanisms by which both heterozygous peroxisome proliferator- activated receptor gamma (PPARgamma) deficiency and PPARgamma agonist improve insulin resistance (2001) J Biol Chem, 276, pp. 41245-41254; Wilson-Fritch, L., Burkart, A., Bell, G., Mendelson, K., Leszyk, J., Nicoloro, S., Czech, M., Corvera, S., Mitochondrial biogenesis and remodeling during adipogenesis and in response to the insulin sensitizer rosiglitazone (2003) Molecular and Cellular Biology, 23 (3), pp. 1085-1094. , DOI 10.1128/MCB.23.3.1085-1094.2003; Ducluzeau, P.H., Priou, M., Weitheimer, M., Flamment, M., Duluc, L., Iacobazi, F., Soleti, R., Malthièry, Y., Dynamic regulation of mitochondrial network and oxidative functions during 3T3-L1 fat cell differentiation (2011) J Physiol Biochem, 67, pp. 285-296; Bogacka, I., Ukropcova, B., McNeil, M., Gimble, J.M., Smith, S.R., Structural and functional consequences of mitochondrial biogenesis in human adipocytes in vitro (2005) Journal of Clinical Endocrinology and Metabolism, 90 (12), pp. 6650-6656. , http://jcem.endojournals.org/cgi/reprint/90/12/6650, DOI 10.1210/jc.2005-1024; Toda, S., Uchihashi, K., Aoki, S., Sonoda, E., Yamasaki, F., Piao, M., Ootani, A., Sugihara, H., Adipose tissueorganotypic culture system as a promising model for studying adipose tissue biology and regeneration (2009) Organogenesis, 5, pp. 50-56; Tuxhorn, J.A., Ayala, G.E., Rowley, D.R., Reactive stroma in prostate cancer progression (2001) Journal of Urology, 166 (6), pp. 2472-2483
Keywords: Adipokines; adiponectin; adipose tissue; adult; article; cancer cell; cancer growth; Cells, Cultured; clinical article; controlled study; Culture Media, Conditioned; culture medium; Cytokines; DNA, Mitochondrial; enzyme activity; enzyme linked immunosorbent assay; explant; gelatinase B; human; human cell; human tissue; Humans; interleukin 6; Interleukin-6; male; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9; Middle Aged; mitochondrial DNA; Osteopontin; Periprostatic adipose tissue; priority journal; Prostate cancer; Prostatic Neoplasms; protein expression; protein induction; protein secretion; quantitative analysis; stroma cell; tissue metabolism; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

The Arabidopsis D-Type Cyclin CYCD2;1 and the Inhibitor ICK2/KRP2 Modulate Auxin-Induced Lateral Root Formation - Sanz, L.; Dewitte, W.; Forzani, C.; Patell, F.; Nieuwland, J.; Wen, B.; Quelhas, P.; de Jager, S.; Titmus, C.; Campilho, A.; Ren, H.; Estelle, M.; et al. (Plant CellPlant Cell, 2011)
The integration of cell division in root growth and development requires mediation of developmental and physiological signals through regulation of cyclin-dependent kinase activity. Cells within the pericycle form de novo lateral root meristems, and D-type cyclins (CYCD), as regulators of the G 1-to-S phase cell cycle transition, are anticipated to play a role. Here, we show that the D-type cyclin protein CYCD2;1 is nuclear in Arabidopsis thaliana root cells, with the highest concentration in apical and lateral meristems. Loss of CYCD2;1 has a marginal effect on unstimulated lateral root density, but CYCD2;1 is rate-limiting for the response to low levels of exogenous auxin. However, while CYCD2;1 expression requires sucrose, it does not respond to auxin. The protein Inhibitor-Interactor of CDK/Kip Related Protein2 (ICK2/KRP2), which interacts with CYCD2;1, inhibits lateral root formation, and ick2/krp2 mutants show increased lateral root density. ICK2/ KRP2 can modulate the nuclear levels of CYCD2;1, and since auxin reduces ICK2/KRP2 protein levels, it affects both activity and cellular distribution of CYCD2;1. Hence, as ICK2/KRP2 levels decrease, the increase in lateral root density depends on CYCD2;1, irrespective of ICK2/CYCD2;1 nuclear localization. We propose that ICK2/KRP2 restrains root ramification by maintaining CYCD2;1 inactive and that this modulates pericycle responses to auxin fluctuations. © 2011 American Society of Plant Biologists.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: PLCEEdoi: 10.1105/tpc.110.080002PubMed ID: 21357490Language of Original Document: EnglishCorrespondence Address: Murray, J. A. H.; Cardiff School of Biosciences, Cardiff University, CF10 3AX Cardiff, United Kingdom; email: murrayja1@cardiff.ac.ukChemicals/CAS: proteasome, 140879-24-9; ATP dependent 26S protease, 3.4.99.-; Arabidopsis Proteins; Cell Cycle Proteins; CycD2 protein, Arabidopsis; Cyclins; ICK2 protein, Arabidopsis; Indoleacetic Acids; Proteasome Endopeptidase Complex, 3.4.25.1References: Achard, P., Gusti, A., Cheminant, S., Alioua, M., Dhondt, S., Coppens, F., Beemster, G.T., Genschik, P., Gibberellin signaling controls cell proliferation rate in Arabidopsis (2009) Curr. Biol., 19, pp. 1188-1193;Alonso, J.M., Genome-wide insertional mutagenesis of Arabidopsis thaliana (2003) Science, 301, pp. 653-657; Baluska, F., Mancuso, S., Volkmann, D., Barlow, P.W., Root apex transition zone: A signalling-response nexus in the root (2010) Trends Plant Sci., 15, pp. 402-408; Bechtold, N., Pelletier, G., In planta Agrobacterium-mediated transformation of adult Arabidopsis thaliana plants by vacuum infiltration (1998) Methods Mol. Biol., 82, pp. 259-266; Bird, D.A., Buruiana, M.M., Zhou, Y., Fowke, L.C., Wang, H., Arabidopsis cyclin-dependent kinase inhibitors are nuclearlocalized and show different localization patterns within the nucleoplasm (2007) Plant Cell Rep., 26, pp. 861-872; Boerjan, W., Cervera, M.T., Delarue, M., Beeckman, T., Dewitte, W., Bellini, C., Caboche, M., Inzé, D., Superroot, a recessive mutation in Arabidopsis, confers auxin overproduction (1995) Plant Cell, 7, pp. 1405-1419; Boisnard-Lorig, C., Colon-Carmona, A., Bauch, M., Hodge, S., Doerner, P., Bancharel, E., Dumas, C., Berger, F., Dynamic analyses of the expression of the HISTONE:YFP fusion protein in Arabidopsis show that syncytial endosperm is divided in mitotic domains (2001) Plant Cell, 13, pp. 495-509; Boniotti, M.B., Gutierrez, C., A cell-cycle-regulated kinase activity phosphorylates plant retinoblastoma protein and contains, in Arabidopsis, a CDKA/cyclin D complex (2001) Plant J., 28, pp. 341-350; Boruc, J., Van den Daele, H., Hollunder, J., Rombauts, S., Mylle, E., Hilson, P., Inzé, D., Russinova, E., Functional modules in the Arabidopsis core cell cycle binary proteinprotein interaction network (2010) Plant Cell, 22, pp. 1264-1280; Brady, S.M., Orlando, D.A., Lee, J.Y., Wang, J.Y., Koch, J., Dinneny, J.R., Mace, D., Benfey, P.N., A high-resolution root spatiotemporal map reveals dominant expression patterns (2007) Science, 318, pp. 801-806; Casimiro, I., Beeckman, T., Graham, N., Bhalerao, R., Zhang, H., Casero, P., Sandberg, G., Bennett, M.J., Dissecting Arabidopsis lateral root development (2003) Trends Plant Sci., 8, pp. 165-171; Casimiro, I., Marchant, A., Bhalerao, R.P., Beeckman, T., Dhooge, S., Swarup, R., Graham, N., Bennett, M., Auxin transport promotes Arabidopsis lateral root initiation (2001) Plant Cell, 13, pp. 843-852; Chevray, P.M., Nathans, D., Protein interaction cloning in yeast: Identification of mammalian proteins that react with the leucine zipper of Jun (1992) Proc. Natl. Acad. Sci. USA, 89, pp. 5789-5793; Churchman, M.L., SIAMESE, a plant-specific cell cycle regulator, controls endoreplication onset in Arabidopsis thaliana (2006) Plant Cell, 18, pp. 3145-3157; Cleary, A., Fowke, L., Wang, H., John, P., The effect of ICK1, a plant cyclin-dependent kinase inhibitor, on mitosis in living plant cells (2002) Plant Cell Rep., 20, pp. 814-820; Clough, S.J., Bent, A.F., Floral dip: A simplified method for Agrobacterium-mediated transformation of Arabidopsis thaliana (1998) Plant J., 16, pp. 735-743; Cockcroft, C.E., den Boer, B.G., Healy, J.M., Murray, J.A.H., Cyclin D control of growth rate in plants (2000) Nature, 405, pp. 575-579; de Smet, I., Vanneste, S., Inzé, D., Beeckman, T., Lateral root initiation or the birth of a new meristem (2006) Plant Mol. Biol., 60, pp. 871-887; de Smet, I., Auxin-dependent regulation of lateral root positioning in the basal meristem of Arabidopsis (2007) Development, 134, pp. 681-690; de Smet, I., Bimodular auxin response controls organogenesis (2010) Proc. Natl. Acad. Sci. USA, 107, pp. 2705-2710; de Veylder, L., Beeckman, T., Beemster, G.T., de Almeida Engler, J., Ormenese, S., Maes, S., Naudts, M., Inzé, D., Control of proliferation, endoreduplication and differentiation by the Arabidopsis E2Fa-DPa transcription factor (2002) EMBO J., 21, pp. 1360-1368; de Veylder, L., Beeckman, T., Beemster, G.T., Krols, L., Terras, F., Landrieu, I., van der Schueren, E., Inzé, D., Functional analysis of cyclin-dependent kinase inhibitors of Arabidopsis (2001) Plant Cell, 13, pp. 1653-1668; de Veylder, L., de Almeida Engler, J., Burssens, S., Manevski, A., Lescure, B., Van Montagu, M., Engler, G., Inzé, D., A new D-type cyclin of Arabidopsis thaliana expressed during lateral root primordia formation (1999) Planta, 208, pp. 453-462; Dewitte, W., Murray, J.A.H., The plant cell cycle (2003) Annu. Rev. Plant Biol., 54, pp. 235-264; Dewitte, W., Riou-Khamlichi, C., Scofield, S., Healy, J.M., Jacqmard, A., Kilby, N.J., Murray, J.A.H., Altered cell cycle distribution, hyperplasia, and inhibited differentiation in Arabidopsis caused by the D-type cyclin CYCD3 (2003) Plant Cell, 15, pp. 79-92; Dewitte, W., Scofield, S., Alcasabas, A.A., Maughan, S.C., Menges, M., Braun, N., Collins, C., Murray, J.A.H., Arabidopsis CYCD3 D-type cyclins link cell proliferation and endocycles and are rate-limiting for cytokinin responses (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 14537-14542; Dharmasiri, N., Dharmasiri, S., Weijers, D., Karunarathna, N., Jurgens, G., Estelle, M., AXL and AXR1 have redundant functions in RUB conjugation and growth and development in Arabidopsis (2007) Plant J., 52, pp. 114-123; Ditengou, F.A., Teale, W.D., Kochersperger, P., Flittner, K.A., Kneuper, I., van der Graaff, E., Nziengui, H., Palme, K., Mechanical induction of lateral root initiation in Arabidopsis thaliana (2008) Proc. Natl. Acad. Sci. USA, 105, pp. 18818-18823; Dubrovsky, J.G., Rost, T.L., Colón-Carmona, A., Doerner, P., Early primordium morphogenesis during lateral root initiation in Arabidopsis thaliana (2001) Planta, 214, pp. 30-36; Dubrovsky, J.G., Sauer, M., Napsucialy-Mendivil, S., Ivanchenko, M.G., Friml, J., Shishkova, S., Celenza, J., Benková, E., Auxin acts as a local morphogenetic trigger to specify lateral root founder cells (2008) Proc. Natl. Acad. Sci. USA, 105, pp. 8790-8794; Duttweiler, H.M., A highly sensitive and non-lethal beta-galactosidase plate assay for yeast (1996) Trends Genet., 12, pp. 340-341; Ebel, C., Mariconti, L., Gruissem, W., Plant retinoblastoma homologues control nuclear proliferation in the female gametophyte (2004) Nature, 429, pp. 776-780; Fukaki, H., Tameda, S., Masuda, H., Tasaka, M., Lateral root formation is blocked by a gain-of-function mutation in the SOLITARY-ROOT/IAA14 gene of Arabidopsis (2002) Plant J., 29, pp. 153-168; Fukaki, H., Tasaka, M., Hormone interactions during lateral root formation (2009) Plant Mol. Biol., 69, pp. 437-449; Healy, J.M., Menges, M., Doonan, J.H., Murray, J.A.H., The Arabidopsis D-type cyclins CycD2 and CycD3 both interact in vivo with the PSTAIRE cyclin-dependent kinase Cdc2a but are differentially controlled (2001) J. Biol. Chem., 276, pp. 7041-7047; Himanen, K., Boucheron, E., Vanneste, S., de Almeida Engler, J., Inzé, D., Beeckman, T., Auxin-mediated cell cycle activation during early lateral root initiation (2002) Plant Cell, 14, pp. 2339-2351; Himanen, K., Vuylsteke, M., Vanneste, S., Vercruysse, S., Boucheron, E., Alard, P., Chriqui, D., Beeckman, T., Transcript profiling of early lateral root initiation (2004) Proc. Natl. Acad. Sci. USA, 101, pp. 5146-5151; Hirano, H., Harashima, H., Shinmyo, A., Sekine, M., Arabidopsis RETINOBLASTOMA-RELATED PROTEIN 1 is involved in G1 phase cell cycle arrest caused by sucrose starvation (2008) Plant Mol. Biol., 66, pp. 259-275; Huntley, R., The maize retinoblastoma protein homologue ZmRb-1 is regulated during leaf development and displays conserved interactions with G1/S regulators and plant cyclin D (CycD) proteins (1998) Plant Mol. Biol., 37, pp. 155-169; Inzé, D., De Veylder, L., Cell cycle regulation in plant development (2006) Annu. Rev. Genet., 40, pp. 77-105; Jakoby, M.J., Weinl, C., Pusch, S., Kuijt, S.J., Merkle, T., Dissmeyer, N., Schnittger, A., Analysis of the subcellular localization, function, and proteolytic control of the Arabidopsis cyclin-dependent kinase inhibitor ICK1/KRP1 (2006) Plant Physiol., 141, pp. 1293-1305; James, P., Halladay, J., Craig, E.A., Genomic libraries and a host strain designed for highly efficient two-hybrid selection in yeast (1996) Genetics, 144, pp. 1425-1436; Jasinski, S., Riou-Khamlichi, C., Roche, O., Perennes, C., Bergounioux, C., Glab, N., The CDK inhibitor NtKIS1a is involved in plant development, endoreduplication and restores normal development of cyclin D3;1-overexpressing plants (2002) J. Cell Sci., 115, pp. 973-982; Karimi, M., Depicker, A., Hilson, P., Recombinational cloning with plant gateway vectors (2007) Plant Physiol., 145, pp. 1144-1154; Kohalmi, S.E., Nowak, J., Crosby, W.L., The yeast twohybrid system (1997) Differentially Expressed Genes in Plants: A Bench Manual, pp. 63-82. , In, E. Hansen and G. Harper, eds (London: Taylor & Francis); Laskowski, M., Grieneisen, V.A., Hofhuis, H., Hove, C.A., Hogeweg, P., Marée, A.F., Scheres, B., Root system architecture from coupling cell shape to auxin transport (2008) PLoS Biol., 6, pp. e307; Laskowski, M.J., Williams, M.E., Nusbaum, H.C., Sussex, I.M., Formation of lateral root meristems is a two-stage process (1995) Development, 121, pp. 3303-3310; Lechner, E., Xie, D., Grava, S., Pigaglio, E., Planchais, S., Murray, J.A.H., Parmentier, Y., Genschik, P., The AtRbx1 protein is part of plant SCF complexes, and its down-regulation causes severe growth and developmental defects (2002) J. Biol. Chem., 277, pp. 50069-50080; Lincoln, C., Britton, J.H., Estelle, M., Growth and development of the axr1 mutants of Arabidopsis (1990) Plant Cell, 2, pp. 1071-1080; López-Bucio, J., Cruz-Ramírez, A., Herrera-Estrella, L., The role of nutrient availability in regulating root architecture (2003) Curr. Opin. Plant Biol., 6, pp. 280-287; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., Automated Arabidopsis plant root cell segmentation based on SVM classification and region merging (2009) Comput. Biol. Med., 39, pp. 785-793; Masubelele, N.H., Dewitte, W., Menges, M., Maughan, S., Collins, C., Huntley, R., Nieuwland, J., Murray, J.A.H., D-type cyclins activate division in the root apex to promote seed germination in Arabidopsis (2005) Proc. Natl. Acad. Sci. USA, 102, pp. 15694-15699; Menges, M., de Jager, S.M., Gruissem, W., Murray, J.A.H., Global analysis of the core cell cycle regulators of Arabidopsis identifies novel genes, reveals multiple and highly specific profiles of expression and provides a coherent model for plant cell cycle control (2005) Plant J., 41, pp. 546-566; Menges, M., Samland, A.K., Planchais, S., Murray, J.A.H., The D-type cyclin CYCD3;1 is limiting for the G1-to-S-phase transition in Arabidopsis (2006) Plant Cell, 18, pp. 893-906; Minet, M., Dufour, M.E., Lacroute, F.B., Complementation of Saccharomyces cerevisiae auxotrophic mutants by Arabidopsis thaliana cDNAs (1992) Plant J., 2, pp. 417-422; Moreno-Risueno, M.A., Van Norman, J.M., Moreno, A., Zhang, J., Ahnert, S.E., Benfey, P.N., Oscillating gene expression determines competence for periodic Arabidopsis root branching (2010) Science, 329, pp. 1306-1311; Nieuwland, J., Maughan, S., Dewitte, W., Scofield, S., Sanz, L., Murray, J.A.H., The D-type cyclin CYCD4;1 modulates lateral root density in Arabidopsis by affecting the basal meristem region (2009) Proc. Natl. Acad. Sci. USA, 106, pp. 22528-22533; Okushima, Y., Fukaki, H., Onoda, M., Theologis, A., Tasaka, M., ARF7 and ARF19 regulate lateral root formation via direct activation of LBD/ASL genes in Arabidopsis (2007) Plant Cell, 19, pp. 118-130; Péret, B., De Rybel, B., Casimiro, I., Benková, E., Swarup, R., Laplaze, L., Beeckman, T., Bennett, M.J., Arabidopsis lateral root development: An emerging story (2009) Trends Plant Sci., 14, pp. 399-408; Petersson, S.V., Johansson, A.I., Kowalczyk, M., Makoveychuk, A., Wang, J.Y., Moritz, T., Grebe, M., Ljung, K., An auxin gradient and maximum in the Arabidopsis root apex shown by high-resolution cell-specific analysis of IAA distribution and synthesis (2009) Plant Cell, 21, pp. 1659-1668; Petroski, M.D., Deshaies, R.J., Function and regulation of cullin-RING ubiquitin ligases (2005) Nat. Rev. Mol. Cell Biol., 6, pp. 9-20; Planchais, S., Samland, A.K., Murray, J.A.H., Differential stability of Arabidopsis D-type cyclins: CYCD3;1 is a highly unstable protein degraded by a proteasome-dependent mechanism (2004) Plant J., 38, pp. 616-625; Qi, R., John, P.C., Expression of genomic AtCYCD2;1 in Arabidopsis induces cell division at smaller cell sizes: Implications for the control of plant growth (2007) Plant Physiol., 144, pp. 1587-1597; Ren, H., Santner, A., del Pozo, J.C., Murray, J.A.H., Estelle, M., Degradation of the cyclin-dependent kinase inhibitor KRP1 is regulated by two different ubiquitin E3 ligases (2008) Plant J., 53, pp. 705-716; Richter, G.L., Monshausen, G.B., Krol, A., Gilroy, S., Mechanical stimuli modulate lateral root organogenesis (2009) Plant Physiol., 151, pp. 1855-1866; Riou-Khamlichi, C., Huntley, R., Jacqmard, A., Murray, J.A.H., Cytokinin activation of Arabidopsis cell division through a D-type cyclin (1999) Science, 283, pp. 1541-1544; Riou-Khamlichi, C., Menges, M., Healy, J.M., Murray, J.A.H., Sugar control of the plant cell cycle: Differential regulation of Arabidopsis D-type cyclin gene expression (2000) Mol. Cell. Biol., 20, pp. 4513-4521; Sabatini, S., Beis, D., Wolkenfelt, H., Murfett, J., Guilfoyle, T., Malamy, J., Benfey, P., Scheres, B., An auxin-dependent distal organizer of pattern and polarity in the Arabidopsis root (1999) Cell, 99, pp. 463-472; Schnittger, A., Schöbinger, U., Bouyer, D., Weinl, C., Stierhof, Y.D., Hülskamp, M., Ectopic D-type cyclin expression induces not only DNA replication but also cell division in Arabidopsis trichomes (2002) Proc. Natl. Acad. Sci. USA, 99, pp. 6410-6415; van Leene, J., Targeted interactomics reveals a complex core cell cycle machinery in Arabidopsis thaliana (2010) Mol. Syst. Biol., 6, p. 397; Vanneste, S., Cell cycle progression in the pericycle is not sufficient for SOLITARY ROOT/IAA14-mediated lateral root initiation in Arabidopsis thaliana (2005) Plant Cell, 17, pp. 3035-3050; Verkest, A., Manes, C.L., Vercruysse, S., Maes, S., van der Schueren, E., Beeckman, T., Genschik, P., De Veylder, L., The cyclin-dependent kinase inhibitor KRP2 controls the onset of the endoreduplication cycle during Arabidopsis leaf development through inhibition of mitotic CDKA;1 kinase complexes (2005) Plant Cell, 17, pp. 1723-1736; Verkest, A., Weinl, C., Inzé, D., De Veylder, L., Schnittger, A., Switching the cell cycle. Kip-related proteins in plant cell cycle control (2005) Plant Physiol., 139, pp. 1099-1106; Wang, H., Qi, Q., Schorr, P., Cutler, A.J., Crosby, W.L., Fowke, L.C., ICK1, a cyclin-dependent protein kinase inhibitor from Arabidopsis thaliana interacts with both Cdc2a and CycD3, and its expression is induced by abscisic acid (1998) Plant J., 15, pp. 501-510; Wildwater, M., Campilho, A., Perez-Perez, J.M., Heidstra, R., Blilou, I., Korthout, H., Chatterjee, J., Scheres, B., The RETINOBLASTOMA-RELATED gene regulates stem cell maintenance in Arabidopsis roots (2005) Cell, 123, pp. 1337-1349; Willemse, J., Kulikova, O., de Jong, H., Bisseling, T., A new whole-mount DNA quantification method and the analysis of nuclear DNA content in the stem-cell niche of Arabidopsis roots (2008) Plant J., 55, pp. 886-894; Winter, D., Vinegar, B., Nahal, H., Ammar, R., Wilson, G.V., Provart, N.J., An "Electronic Fluorescent Pictograph" browser for exploring and analyzing large-scale biological data sets (2007) PLoS ONE, 2, pp. e718; Zhou, Y., Fowke, L.C., Wang, H., Plant CDK inhibitors: Studies of interactions with cell cycle regulators in the yeast twohybrid system and functional comparisons in transgenic Arabidopsis plants (2002) Plant Cell Rep., 20, pp. 967-975; Zhou, Y., Niu, H., Brandizzi, F., Fowke, L.C., Wang, H., Molecular control of nuclear and subnuclear targeting of the plant CDK inhibitor ICK1 and ICK1-mediated nuclear transport of CDKA (2006) Plant Mol. Biol., 62, pp. 261-278; Zhou, Y., Wang, H., Gilmer, S., Whitwill, S., Fowke, L.C., Effects of co-expressing the plant CDK inhibitor ICK1 and D-type cyclin genes on plant growth, cell size and ploidy in Arabidopsis thaliana (2003) Planta, 216, pp. 604-613
Keywords: Arabidopsis; Arabidopsis protein; Arabidopsis Proteins; Arabidopsis thaliana; article; ATP dependent 26S protease; cell cycle; cell cycle protein; Cell Cycle Proteins; cell nucleus; CycD2 protein, Arabidopsis; cycline; Cyclins; gene expression regulation; Gene Expression Regulation, Plant; genetics; growth, development and aging; ICK2 protein, Arabidopsis; indoleacetic acid derivative; Indoleacetic Acids; metabolism; mutation; plant root; Plant roots; proteasome; Proteasome Endopeptidase Complex

Arabidopsis thaliana automatic cell file detection and cell length estimation - Quelhas, P.; Nieuwland, J.; Dewitte, W.; Mendonça, A.M.; Murray, J.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
In plant development biology, the study of the structure of the plant's root is fundamental for the understanding of the regulation and interrelationships of cell division and cellular differentiation. This is based on the high connection between cell length and progression of cell differentiation and the nuclear state. However, the need to analyse a large amount of images from many replicate roots to obtain reliable measurements motivates the development of automatic tools for root structure analysis. We present a novel automatic approach to detect cell files, the main structure in plant roots, and extract the length of the cells in those files. This approach is based on the detection of local cell file characteristic symmetry using a wavelet based image symmetry measure. The resulting detection enables the automatic extraction of important data on the plant development stage and of characteristics for individual cells. Furthermore, the approach presented reduces in more than 90% the time required for the analysis of each root, improving the work of the biologist and allowing the increase of the amount of data to be analysed for each experimental condition. While our approach is fully automatic a user verification and editing stage is provided so that any existing errors may be corrected. Given five test images it was observed that user did not correct more than 20% of all automatically detected structure, while taking no more than 10% of manual analysis time to do so. © 2011 Springer-Verlag.
Conference code: 85546Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-21596-4_1Language of Original Document: EnglishCorrespondence Address: Quelhas, P.; INEB - Divisão de Sinal e Imagem, Instituto de Engenharia Biomédica, Porto, PortugalReferences: Terpstra, I., Heidstra, R., Stem cells: The root of all cells (2009) Semin. Cell Dev. Biol., 20 (9), pp. 1089-1096;Bennett, T., Scheres, B., Root development-two meristems for the price of one? (2010) Curr. Top Dev. Bio., 91, pp. 67-102; De Smet, I., Tetsumura, T., De Rybel, B., Frey, N.F., Laplaze, L., Casimiro, I., Swarup, R., Beeckman, T., Auxin-dependent regulation of lateral root positioning in the basal meristem of arabidopsis (2007) Development, 134 (4), pp. 681-690; Nieuwland, J., Maughan, S., Dewitte, W., Scofield, S., Sanz, L., Murray, J.A., The d-type cyclin cycd4;1 modulates lateral root density in arabidopsis by affecting the basal meristem region (2009) Proc. Natl. Acad. Sci. U S A, 106 (52), pp. 22528-22533; Vanstraelen, M., Baloban, M., Da Ines, O., Cultrone, A., Lammens, T., Boudolf, V., Brown, S.C., Kondorosi, E., Apc/c-ccs52a complexes control meristem maintenance in the arabidopsis root (2009) Proc. Natl. Acad. Sci. U S A, 106 (28), pp. 11806-11811; Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res., 119, pp. 85-93; Immink, R., Gadella, T., Ferrario, S., Busscher, M., Angenent, G., Analysis of mads box protein-protein interactions in living plant cells (2002) Proc. Natl. Acad. Sci. USA, 99, pp. 2416-2421; Willemse, J., Kulikova, O., Jong, H., Bisseling, T., A new whole-mount dna quantification method and the analysis of nuclear dna content in the stem-cell niche of arabidopsis roots (2008) The Plant Journal, 10, pp. 1365-1374; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., Automated arabidopsis plant root cell segmentation based on svm classification and region merging (2009) Comp. in Biology and Medicine, 39, pp. 785-793; Marcuzzo, M., Guichard, T., Quelhas, P., Mendonça, A.M., Campilho, A., Cell division detection on the arabidopsis thaliana root (2009) LNCS, 5524, pp. 168-175. , Araujo, H., Mendonça, A.M., Pinho, A.J., Torres, M.I. (eds.) IbPRIA 2009. Springer, Heidelberg; Kovesi, P., Symmetry and asymmetry from local phase Proc. of the 10th Australian Joint Conf. on Artificial Intelligence (December 1997); Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Trans. on Image Processing, 16 (8), pp. 2080-2095; Otsu, N., A threshold selection method from gray-level histograms (1979) IEEE Transactions on Systems, Man, and Cybernetics, SMC-9 (1), pp. 62-66
Keywords: Arabidopsis thaliana; Automatic extraction; Automatic tools; Bio-imaging; BioImaging; cell differentiation; Cell divisions; Cell lengths; cell proliferation; Cells; Cellular differentiation; Experimental conditions; Image analysis; image symmetry; Individual cells; Main structure; Manual analysis; Nuclear state; Plant development; Plant roots; Plants (botany); Reliable measurement; Root structure; Test images; User verification; Wavelet analysis; Wavelet-based images

Automatic and semi-automatic analysis of the extension of myocardial infarction in an experimental murine model - Esteves, T.; Valente, M.; Nascimento, D.S.; Pinto-Do-Ó, P.; Quelhas, P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
Rodent models of myocardial infarction (MI) have been extensively used in biomedical research towards the implementation of novel regenerative therapies. Permanent ligation of the left anterior descending (LAD) coronary artery is a commonly used method for inducing MI both in rat and mouse. Post-mortem evaluation of the heart, particularly the MI extension assessment performed on histological sections, is a critical parameter for this experimental setting. MI extension, which is defined as the percentage of the left ventricle affected by the coronary occlusion, has to be estimated by identifying the infarcted- and the normal-tissue in each section. However, because it is a manual procedure it is time-consuming, arduous and prone to bias. Herein, we introduce semi-automatic and automatic approaches to perform segmentation which is then used to obtain the infarct extension measurement. Experimental validation is performed comparing the proposed approaches with manual annotation and a total error not exceeding 8% is reported in all cases. © 2011 Springer-Verlag.
Conference code: 85429Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-21257-4_19Language of Original Document: EnglishCorrespondence Address: Esteves, T.; Departamento de Engenharia Electrotécnica e de Computadores, Faculdade de Engenharia, Universidade Do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: meb09026@fe.up.ptReferences: Degabriele, N., Griesenbach, U., Sato, K., Critical appraisal of the mouse model of myocardial infarction (2004) Experimental Physiology, 89 (4), pp. 497-505;Takagawa, J., Zhang, Y., Wong, M., Myocardial infarct size measurement in the mouse chronic infarction model: Comparison of area- and length-based approaches (2007) Journal of Applied Physiology, 102, pp. 2104-2111; Alattar, M., Osman, N., Fahmy, A., Myocardial segmentation using constrained multi-seeded region growing (2010) LNCS, 6112, pp. 89-98. , Campilho, A., Kamel, M. (eds.) ICIAR 2010 Springer, Heidelberg; Wu, Q., Merchant, F., Castleman, K., (1996) Microscope Image Processing, , ch. 7. Elsevier, Amsterdam; Gonzalez, R., Woods, R., Eddins, S., (2004) Digital Image Processing Using MATLAB, , ch. 9. Pearson Education, London; Sharma, N., Aggarwal, L., Automated medical image segmentation techniques (2010) Journal of Medical Physics, 35 (1), pp. 3-14; Pham, D., Xu, C., A survey of current methods in medical image segmentation (1998) Annual Review of Biomedical Engineering, 2, pp. 315-338; Hamarneh, G., Li, X., Watershed segmentation using prior shape and appearance knowledge (2009) Image and Vision Comp, 27 (1-2), pp. 59-68; Khadir, S., Ahamed, R., Moving toward region-based image segmentation techniques: A study (2009) Journal of Theoretical and Applied Information Technology, 5 (1), pp. 1-7; Ahmed, M., Mohamad, D., Segmentation of brain mr images for tumor extraction by combining kmeans clustering and perona-malik anisotropic diffusion model (2010) International Journal of Image Processing, 2 (1), pp. 1-8; Mayer, A., Greenspan, H., An adaptive mean-shift framework for MRI brain segmentation (2009) IEEE Trans. on Medical Imaging, 28 (8), pp. 1-12; Dabov, K., Foi, A., Katkovnik, V., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Trans. on Image Processing, 16 (8), pp. 1-16; Otsu, N., A threshold selection method from gray level histograms (1979) IEEE Trans. Systems, Man and Cybernetics, 9 (1), pp. 62-66; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., Automated arabidopsis plant root cell segmentation based on svm classification and region merging (2009) Computers in Biology and Medicine, 39 (9), pp. 1-9; Bleau, A., Leon, J., Watershed-based segmentation and region merging (2000) Computer Vision and Image Understanding, 77 (3), pp. 317-370
Keywords: Extension evaluations; Image analysis; Image segmentation; Infarct extension evaluation; k-means; Mammals; meanshift; otsu; Pattern recognition; region growing; Tissue; watershed

Automatic and semi-automatic analysis of the extension of myocardial infarction in an experimental murine model - Esteves, T.; Valente, M.; Nascimento, D.S.; Pinto-Do-Ó, P.; Quelhas, P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2011)
Cited By (since 1996):1Export Date: 2 October 2013Source: Scopus

Automatic segmentation of chromatographic images for region of interest delineation - Mendonça, A.M.; Sousa, A.V.; Sá-Miranda, M.C.; Campilho, A.C. (Progress in Biomedical Optics and Imaging - Proceedings of SPIEProgr. Biomed. Opt. Imaging Proc. SPIE, 2011)
This paper describes a segmentation method for automating the region of interest (ROI) delineation in chromatographic images, thus allowing the definition of the image area that contains the fundamental information for further processing while excluding the frame of the chromatographic plate that does not contain relevant data for disease identification. This is the first component of a screening tool for Fabry disease, which will be based on the automatic analysis of the chromatographic patterns extracted from the image ROI. Image segmentation is performed in two phases, where each individual pixel is finally considered as frame or ROI. In the first phase, an unsupervised learning method is used for classifying image pixels into three classes: frame, ROI or unknown. In the second phase, distance features are used for deciding which class the unknown pixels belong to. The segmentation result is post-processed using a sequence of morphological operators in order to obtain the final ROI rectangular area. The proposed methodology was successfully evaluated in a dataset of 41 chromatographic images. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
Conference code: 84913Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 79623Bdoi: 10.1117/12.877671Language of Original Document: EnglishCorrespondence Address: Mendonça, A. M.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: amendon@fe.up.ptReferences: Zarate, Y., Hopkin, R., Fabry's disease (2008) The Lancet, 372 (9647), pp. 1427-1435;Gerasimov, A.V., Use of the Software Processing of Scanned Chromatogram Images in Quantitative Planar Chromatography (2004) J. of Anal Chem., 59 (4), pp. 348-353; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput Methods Programs Biomed, 77 (3), pp. 209-231; Sousa, A.V., Mendonca, A.M., Campilho, A., Chromatographic pattern classification (2008) IEEE Trans on Biomedical Engineering, 55 (6), pp. 1687-1696; Bajla, I., Rublík, F., Arendacká, B., Farkaš, I., Hornišová, K., Štolc, S., Witkovský, V., Segmentation and supervised classification of image objects in Epo doping-control (2009) Machine Vision and Applications, 20 (4), pp. 243-259; Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of Thin-Layer Chromatography (2004) LNCS, 3212, pp. 158-216. , Springer; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from incomplete data via the EM algorithm (1977) J. of the Royal Statistical Society. Series B, 39 (1), pp. 1-38; Heijden, F., Duin, R.P.W., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation - An Engineering Approach Using Matlab, , John Wiley & Sons Sponsors: The Society of Photo-Optical Instrumentation Engineers (SPIE); Dynasil Corporation/RMD Research; American Association of Physicists in Medicine (AAPM); DQE Instruments, Inc.; Ocean Thin Films, Inc.
Keywords: Automatic analysis; Automatic segmentations; Chromatographic images; Chromatographic plates; Chromatography; Data sets; Distance feature; Fabry disease; Image pixels; Image segmentation; Imaging systems; Medical imaging; Morphological operator; Pixels; Rectangular area; Region of interest; Region of interest delineation; Screening tool; Second phase; Segmentation methods; Segmentation results; Unsupervised learning; Unsupervised learning method

Bone marrow-derived endothelial progenitors expressing delta-like 4 (Dll4) regulate tumor angiogenesis - Real, C.; Remédio, L.; Caiado, F.; Igreja, C.; Borges, C.; Trindade, A.; Pinto-Do-Ó, P.; Yagita, H.; Duarte, A.; Dias, S. (PLoS ONEPLoS ONE, 2011)
Neo-blood vessel growth (angiogenesis), which may involve the activation of pre-existing endothelial cells (EC) and/or the recruitment of bone marrow-derived vascular precursor cells (BM-VPC), is essential for tumor growth. Molecularly, besides the well established roles for Vascular endothelial growth factor (VEGF), recent findings show the Notch signalling pathway, in particular the ligand Delta-like 4 (Dll4), is also essential for adequate tumor angiogenesis; Dll4 inhibition results in impaired, non-functional, angiogenesis and reduced tumor growth. However, the role of BM-VPC in the setting of Notch pathway modulation was not addressed and is the subject of the present report. Here we show that SDF-1 and VEGF, which are produced by tumors, increase Dll4 expression on recruited BM-VPC. Mechanistically, BM-VPC activated, in a Dll4-dependent manner, a transcriptional program on mature EC suggestive of EC activation and stabilization. BM-VPC induced ICAM-2 and Fibronectin expression on EC, an effect that was blocked by a Dll4-specific neutralizing antibody. In vivo, transplantation of BM-VPC with decreased Dll4 into tumor-bearing mice resulted in the formation of microvessels with decreased pericyte coverage and reduced fibronectin expression. Consequently, transplantation of BM-VPC with decreased Dll4 resulted in impaired tumor angiogenesis, increased tumor hypoxia and apoptosis, and decreased tumor growth. Taken together, our data suggests that Dll4 expression by BM-VPC affects their communication with tumor vessel endothelial cells, thereby modulating tumor angiogenesis by affecting vascular stability. © 2011 Real et al.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusArt. No.: e18323doi: 10.1371/journal.pone.0018323Language of Original Document: EnglishCorrespondence Address: Dias, S.; Angiogenesis Laboratory, CIPM/Portuguese Institute of Oncology, Lisbon, Portugal; email: sergidias@ipolisboa.min-saude.ptChemicals/CAS: fibronectin, 86088-83-7; vasculotropin, 127464-60-2; DLL4 protein, mouse; Intracellular Signaling Peptides and Proteins; Membrane ProteinsReferences: Asahara, T., Masuda, H., Takahashi, T., Kalka, C., Pastore, C., Bone marrow origin of endothelial progenitor cells responsible for postnatal vasculogenesis in physiological and pathological neovascularization (1999) Circ Res, 85, pp. 221-228;Rafii, S., Lyden, D., Benezra, R., Hattori, K., Heissig, B., Vascular and haematopoietic stem cells: Novel targets for anti-angiogenesis therapy? (2002) Nat Rev Cancer, 2, pp. 826-835. , Review; Lyden, D., Hattori, K., Dias, S., Costa, C., Blaikie, P., Impaired recruitment of bone-marrow-derived endothelial and hematopoietic precursor cells blocks tumor angiogenesis and growth (2001) Nat Med, 7, pp. 1194-1201; Larrivee, B., Niessen, K., Pollet, I., Corbel, S.Y., Long, M., Minimal contribution of marrow-derived endothelial precursors to tumor vasculature (2005) J Immunol, 175, pp. 2890-2899; Peters, B.A., Diaz, L.A., Polyak, K., Meszler, L., Romans, K., Contribution of bone marrow-derived endothelial cells to human tumor vasculature (2005) Nat Med, 11, pp. 261-262; Pasquier, E., Dias, S., Endothelial progenitor cells: Hope beyond controversy (2010) Curr Cancer Drug Targets, 10 (8), pp. 914-921; Dudley, A.C., Udagawa, T., Melero-Martin, J.M., Shih, S.C., Curatolo, A., Bone marrow is a reservoir for proangiogenic myelomonocytic cells but not endothelial cells in spontaneous tumors (2010) Blood, 116 (17), pp. 2267-2271; Krebs, L.T., Xue, Y., Norton, C.R., Shutter, J.R., Maguire, M., Notch signaling is essential for vascular morphogenesis in mice (2000) Genes Dev, 14, pp. 1343-1352; Uyttendaele, H., Ho, J., Rossant, J., Kitajewski, J., Vascular patterning defects associated with expression of activated Notch4 in embryonic endothelium (2001) Proc Natl Acad Sci U S A, 98, pp. 5643-5648; Duarte, A., Hirashima, M., Benedito, R., Trindade, A., Diniz, P., Dosage-sensitive requirement for mouse Dll4 in artery development (2004) Genes Dev, 18, pp. 2474-2478; Gale, N.W., Dominguez, M.G., Noguera, I., Pan, L., Hughes, V., Haploinsufficiency of delta-like 4 ligand results in embryonic lethality due to major defects in arterial and vascular development (2004) Proc Natl Acad Sci U S A, 101, pp. 15949-15954; Carmeliet, P., Ferreira, V., Breier, G., Pollefeyt, S., Kieckens, L., Abnormal blood vessel development and lethality in embryos lacking a single VEGF allele (1996) Nature, 380, pp. 435-439; Mailhos, C., Modlich, U., Lewis, J., Harris, A., Bicknell, R., Delta4, an endothelial specific notch ligand expressed at sites of physiological and tumor angiogenesis (2001) Differentiation, 69, pp. 135-144; Oliner, J., Min, H., Leal, J., Yu, D., Rao, S., Suppression of angiogenesis and tumor growth by selective inhibition of angiopoietin-2 (2004) Cancer Cell, 6, pp. 507-516; Patel, N.S., Li, J.L., Generali, D., Poulsom, R., Cranston, D.W., Up-regulation of delta-like 4 ligand in human tumor vasculature and the role of basal expression in endothelial cell function (2005) Cancer Res, 65, pp. 8690-8697; Williams, C.K., Li, J.L., Murga, M., Harris, A.L., Tosato, G., Up-regulation of the Notch ligand Delta-like 4 inhibits VEGF-induced endothelial cell function (2006) Blood, 107, pp. 931-939; Caiado, F., Real, C., Carvalho, T., Dias, S., Notch pathway modulation on bone marrow-derived vascular precursor cells regulates their angiogenic and wound healing potential (2008) PLoS One, 3, pp. e3752; Escudier, B., Eisen, T., Stadler, W.M., Szczylik, C., Oudard, S., Sorafenib in advanced clear-cell renal-cell carcinoma (2007) N Engl J Med, 356, pp. 125-134; Llovet, J.M., Ricci, S., Mazzaferro, V., Hilgard, P., Gane, E., Sorafenib in advanced hepatocellular carcinoma (2008) N Engl J Med, 359, pp. 378-390; Motzer, R.J., Bukowski, R.M., Targeted therapy for metastatic renal cell carcinoma (2006) J Clin Oncol, 24, pp. 5601-5608; Bergers, G., Hanahan, D., Modes of resistance to anti-angiogenic therapy (2008) Nat Rev Cancer, 8, pp. 592-603; Verheul, H.M., Pinedo, H.M., Possible molecular mechanisms involved in the toxicity of angiogenesis inhibition (2007) Nat Rev Cancer, 7, pp. 475-485; Noguera-Troise, I., Daly, C., Papadopoulos, N.J., Coetzee, S., Boland, P., Blockade of Dll4 inhibits tumour growth by promoting non-productive angiogenesis (2006) Nature, 444, pp. 1032-1037; Ridgway, J., Zhang, G., Wu, Y., Stawicki, S., Liang, W.C., Inhibition of Dll4 signalling inhibits tumour growth by deregulating angiogenesis (2006) Nature, 444, pp. 1083-1087; Moore, M.A., Hattori, K., Heissig, B., Shieh, J.H., Dias, S., Mobilization of endothelial and hematopoietic stem and progenitor cells by adenovector-mediated elevation of serum levels of SDF-1, VEGF, and angiopoietin-1 (2001) Ann N Y Acad Sci, 938, pp. 36-45. , discussion 45-37; Yamaguchi, J., Kusano, K.F., Masuo, O., Kawamoto, A., Silver, M., Stromal cell-derived factor-1 effects on ex vivo expanded endothelial progenitor cell recruitment for ischemic neovascularization (2003) Circulation, 107, pp. 1322-1328; Leslie, J.D., Ariza-McNaughton, L., Bermange, A.L., McAdow, R., Johnson, S.L., Endothelial signalling by the Notch ligand Delta-like 4 restricts angiogenesis (2007) Development, 134, pp. 839-844; Trindade, A., Kumar, S.R., Scehnet, J.S., Lopes-da-Costa, L., Becker, J., Overexpression of delta-like 4 induces arterialization and attenuates vessel formation in developing mouse embryos (2008) Blood, 112, pp. 1720-1729; Huang, M.T., Mason, J.C., Birdsey, G.M., Amsellem, V., Gerwin, N., Endothelial intercellular adhesion molecule (ICAM)-2 regulates angiogenesis (2005) Blood, 106, pp. 1636-1643; Deutsch, U., Schlaeger, T.M., Dehouck, B., Doring, A., Tauber, S., Inducible endothelial cell-specific gene expression in transgenic mouse embryos and adult mice (2008) Exp Cell Res, 314, pp. 1202-1216; Dias, S., Thomas, H., Balkwill, F., Multiple molecular and cellular changes associated with tumour stasis and regression during IL-12 therapy of a murine breast cancer model (1998) Int J Cancer, 75 (1), pp. 151-157; Scott, K.A., Holdsworth, H., Balkwill, F.R., Dias, S., Exploiting changes in the tumour microenvironment with sequential cytokine and matrix metalloprotease inhibitor treatment in a murine breast cancer model (2000) Br J Cancer, 83 (11), pp. 1538-1543
Keywords: angiogenesis; animal; animal cell; animal tissue; Animals; apoptosis; article; blood vessel; Blood Vessels; bone marrow; bone marrow cell; Bone Marrow Cells; cell activation; Cell Line, Tumor; cell proliferation; controlled study; cytology; delta like 4 protein; DLL4 protein, mouse; Endothelial Cells; endothelium cell; Female; Fibronectin; gene expression; gene expression regulation; genetics; human; human cell; Humans; hypoxia; in vitro study; in vivo study; intercellular adhesion molecule 2; Intracellular Signaling Peptides and Proteins; membrane protein; Membrane Proteins; metabolism; Mice; mouse; Mus; neoplasm; Neoplasms; neovascularization (pathology); Neovascularization, Pathologic; neutralizing antibody; nonhuman; Notch receptor; Pathology; pericyte; protein expression; signal peptide; solid tumor; stem cell; stem cell transplantation; Stem cells; stromal cell derived factor 1; tumor cell line; tumor growth; unclassified drug; vascularization; vasculotropin

Classification-based segmentation of the region of interest in chromatographic images - Sousa, A.V.; Mendonça, A.M.; Sá-Miranda, M.C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
This paper proposes a classification-based method for automating the segmentation of the region of interest (ROI) in digital images of chromatographic plates. Image segmentation is performed in two phases. In the first phase an unsupervised learning method classifies the image pixels into three classes: frame, ROI or unknown. In the second phase, distance features calculated for the members of the three classes are used for deciding on the new label, ROI or frame, for each individual connected segment previously classified as unknown.The segmentation result is post-processed using a sequence of morphological operators before obtaining the final ROI rectangular area. The proposed methodology, which is the initial step for the development of a screening tool for Fabry disease, was successfully evaluated in a dataset of 58 chromatographic images. © 2011 Springer-Verlag.
Conference code: 85546Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-21596-4_8Language of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto de Engenharia Biomédica, Universidade Do Porto, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: asousa@eu.ipp.ptReferences: Zarate, Y., Hopkin, R., Fabry's Disease (2008) The Lancet, 372 (9647), pp. 1427-1435;Linthorst, G.E., Vedder, A., Aerts, J.M., Hollak, C.E., Screening for Fabry Disease Using Whole Blood Spots Fails to Identify One-third of Female Carriers (2005) Clinica Chimica Acta, 353 (1-2), pp. 201-203; Eng, C.M., Germain, D.P., Banikazemi, M., Warnock, D.G., Wanner, C., Hopkin, R.J., Bultas, J., Wilcox, W.R., Fabry Disease: Guidelines for the Evaluation and Management of Multi-organ System Involvement (2006) Genetics in Medicine, 8 (9), pp. 539-548; Gerasimov, A.V., Use of the Software Processing of Scanned Chromatogram Images in Quantitative Planar Chromatography (2004) J. of Anal. Chem., 59 (4), pp. 348-353; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An Alternative Method for Electrophoretic Gel Image Analysis in the Gelmaster Software (2005) Comput. Methods Programs Biomed., 77 (3), pp. 209-231; Sousa, A.V., Mendonça, A.M., Campilho, A., Chromatographic Pattern Classification (2008) IEEE Trans. on Biomedical Engineering, 55 (6), pp. 1687-1696; Bajla, I., Rublík, F., Arendacká, B., Farkaš, I., Hornišová, K., Štolc, S., Witkovský, V., Segmentation and Supervised Classification of Image Objects in Epo Doping-control (2009) Machine Vision and Applications, 20 (4), pp. 243-259; Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic Lane and Band Detection in Images of Thin Layer Chromatography (2004) LNCS, 3212, pp. 158-165. , Campilho, A.C., Kamel, M.S. (eds.) ICIAR 2004. Springer, Heidelberg; Mendonça, A.M., Sousa, A.V., Sá-Miranda, M.C., Campilho, A., Automatic segmentation of chromatographic images for region of interest delineation (2011) SPIE Medical Imaging; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from Incomplete Data via the EM Algorithm (1997) J. of the Royal Statistical Society. Series B, 39 (1), pp. 1-38; Heijden, F., Robert, P.W.D., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation, , John Wiley & Sons, Chichester
Keywords: Chromatographic images; Chromatographic plates; Chromatography; Data sets; Digital image; Distance feature; Fabry disease; Image analysis; Image pixels; Image segmentation; Morphological operator; Rectangular area; Region of interest; Region of interest delineation; Screening tool; Second phase; Segmentation results; Unsupervised learning; Unsupervised learning method

Complexity and categorical analysis may improve the interpretation of agreement studies using continuous variables - Costa-Santos, C.; Bernardes, J.; Antunes, L.; Ayres-de-Campos, D. (Journal of Evaluation in Clinical PracticeJ. Eval. Clin. Pract., 2011)
Rationale Complex clinical scenarios involving a high degree of uncertainty frequently lead to a poor agreement over diagnosis and management. However, inconsistent results can be found with the most widely used measures of agreement for continuous variables - the limits of agreement and the intraclass correlation coefficient. Aims and objectives We aim to improve the interpretation of agreement studies using continues variables. Methods and results Evaluation of agreement may be improved by complexity analysis and by categorization of variables, followed by the use of the proportions of agreement. Conclusions The average never characterizes a complex phenomenon and the methods used to access agreement in continuous variables are based on the mean. For future agreement studies, involving complex continuous variables, we recommend a complexity and categorical analysis. © 2011 Blackwell Publishing Ltd.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JECPFdoi: 10.1111/j.1365-2753.2011.01668.xPubMed ID: 21489051Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Department of Biostatistics and Medical Informatics, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG: An International Journal of Obstetrics and Gynaecology, 112 (5), pp. 667-669. , DOI 10.1111/j.1471-0528.2004.00505.x;Khan, K.S., Chien, P.F., Evaluation of a clinical test. I: Assessment of reliability (2001) BJOG, 108, pp. 562-567; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) Journal of Clinical Epidemiology, 58 (3), pp. 215-216. , DOI 10.1016/j.jclinepi.2004.07.007; Costa-Santos, C., Bernardes, J., Ayres-De-Campos, D., Costa, A., Costa, C., The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement (2011) Journal of Clinical Epidemiology, 64 (3), pp. 264-269; Costa-Santos, C., Antunes, L., Souto, A., Bernardes, J., Assessment of disagreement: A new information-based approach (2010) Annals of Epidemiology, 20, pp. 555-561; Luiz, R.R., Costa, A.J.L., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: A new graphical approach (2003) Journal of Clinical Epidemiology, 56 (10), pp. 963-967. , DOI 10.1016/S0895-4356(03)00164-1; Plsek, P.E., Greenhalgh, T., The challenge of complexity in health care (2001) British Medical Journal, 323 (7313), pp. 625-628; Shiell, A., Hawe, P., Gold, L., Complex interventions or complex systems? Implications for health economic evaluation (2008) BMJ, 336 (7656), pp. 1281-1283; Wilson, T., Holt, T., Complexity science: Complexity and clinical care (2001) British Medical Journal, 323 (7314), pp. 685-688; Miles, A., Complexity in medicine and healthcare: People and systems, theory and practice (2009) Journal of Evaluation in Clinical Practice, 15 (3), pp. 409-410; Shannon, Î., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423. , 623- 656; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) International Journal of Gynecology and Obstetrics, 57 (1), pp. 33-37. , DOI 10.1016/S0020-7292(97)02846-4, PII S0020729297028464; Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) British Journal of Obstetrics and Gynaecology, 106, pp. 1307-1310; Rooth, G., Guidelines for the use of fetal monitoring (1987) International Journal of Gynaecology and Obstetrics, 25, pp. 159-167; Grant, J.M., The fetal heart rate is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Müller, R., Büttner, P., A critical discussion of intraclass correlation coefficients (1994) Statistics in Medicine, 13, pp. 2465-2476; Byrt, T., Bishop, J., Carlin, J.B., Bias, prevalence and kappa (1993) Journal of Clinical Epidemiology, 46 (5), pp. 423-429. , DOI 10.1016/0895-4356(93)90018-V; West, B.J., Homeostasis and Gauss statistics: Barriers to understanding natural variability (2010) Journal of Evaluation in Clinical Practice, 16, pp. 403-408; Goncalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Medical and Biological Engineering and Computing, 44 (10), pp. 847-855. , DOI 10.1007/s11517-006-0105-6; Costa Santos, C., Vitanyi, P.M.B., Bernardes, J., Antunes, L., Clustering fetal heart rate tracings by compression (2006) Proceedings - IEEE Symposium on Computer-Based Medical Systems, 2006, pp. 685-690. , DOI 10.1109/CBMS.2006.68, 1647650, Proceedings - 19th IEEE International Symposium on Computer-Based Medical Systems, CBMS 2006
Keywords: article; Biomedical research; Cardiotocography; clinical decision making; clinical practice; complexity; Data Interpretation, Statistical; Decision Making; entropy; Female; fetus heart rate; Heart Rate, Fetal; human; Humans; observer variation; Pregnancy; Pregnancy Outcome; priority journal; Reproducibility of Results; statistical data interpretation; Uncertainty

Covalent immobilization of antimicrobial peptides (AMPs) onto biomaterial surfaces - Costa, F.; Carvalho, I.F.; Montelaro, R.C.; Gomes, P.; Martins, M.C.L. (Acta BiomaterialiaActa Biomater., 2011)
Bacterial adhesion to biomaterials remains a major problem in the medical devices field. Antimicrobial peptides (AMPs) are well-known components of the innate immune system that can be applied to overcome biofilm-associated infections. Their relevance has been increasing as a practical alternative to conventional antibiotics, which are declining in effectiveness. The recent interest focused on these peptides can be explained by a group of special features, including a wide spectrum of activity, high efficacy at very low concentrations, target specificity, anti-endotoxin activity, synergistic action with classical antibiotics, and low propensity for developing resistance. Therefore, the development of an antimicrobial coating with such properties would be worthwhile. The immobilization of AMPs onto a biomaterial surface has further advantages as it also helps to circumvent AMPs' potential limitations, such as short half-life and cytotoxicity associated with higher concentrations of soluble peptides. The studies discussed in the current review report on the impact of covalent immobilization of AMPs onto surfaces through different chemical coupling strategies, length of spacers, and peptide orientation and concentration. The overall results suggest that immobilized AMPs may be effective in the prevention of biofilm formation by reduction of microorganism survival post-contact with the coated biomaterial. Minimal cytotoxicity and long-term stability profiles were obtained by optimizing immobilization parameters, indicating a promising potential for the use of immobilized AMPs in clinical applications. On the other hand, the effects of tethering on mechanisms of action of AMPs have not yet been fully elucidated. Therefore, further studies are recommended to explore the real potential of immobilized AMPs in health applications as antimicrobial coatings of medical devices. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 24Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2010.11.005PubMed ID: 21056701Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; ampicillin, 69-52-3, 69-53-4, 7177-48-2, 74083-13-9, 94586-58-0; carbenicillin, 17230-86-3, 4697-36-3, 4800-94-6; cefazolin, 25953-19-9, 27164-46-1; gentamicin, 1392-48-9, 1403-66-3, 1405-41-0; penicillin G, 1406-05-9, 61-33-6; teicoplanin, 61036-62-2, 61036-64-4; tobramycin, 32986-56-4; vancomycin, 1404-90-6, 1404-93-9; Antimicrobial Cationic Peptides; Biocompatible Materials; Coated Materials, Biocompatible; Immobilized ProteinsReferences: Glinel, K., Jonas, A.M., Jouenne, T., Leprince, J., Galas, L., Huck, W.T., Antibacterial and antifouling polymer brushes incorporating antimicrobial peptide (2009) Bioconj Chem, 20 (1), pp. 71-77;Vila, J., Soriano, A., Mensa, J., Molecular basis of microbial adherence to prosthetic materials. Role of biofilms in prosthesis-associated infection (2008) Enferm Infecc Microbiol Clin, 26 (1), pp. 48-54; Hetrick, E.M., Schoenfisch, M.H., Reducing implant-related infections: Active release strategies (2006) Chemical Society Reviews, 35 (9), pp. 780-789. , DOI 10.1039/b515219b; Darouiche, R.O., Treatment of Infections Associated with Surgical Implants (2004) New England Journal of Medicine, 350 (14), pp. 1422-1429. , DOI 10.1056/NEJMra035415; Zhao, L., Chu, P.K., Zhang, Y., Wu, Z., Antibacterial coatings on titanium implants (2009) J Biomed Mater Res B Appl Biomater, 91 (1), pp. 470-480; Dee, K.C., Puleo, D.A., Bizios, R., (2002) An Introduction to Tissue-biomaterial Interactions, , Wiley-Liss New York; Subramani, K., Jung, R.E., Molenberg, A., Hammerle, C.H., Biofilm on dental implants: A review of the literature (2009) Int J Oral Maxillofac Implants, 24 (4), pp. 616-626; Fey, P.D., Olson, M.E., Current concepts in biofilm formation of Staphylococcus epidermidis (2010) Future Microbiol, 5 (6), pp. 917-933; De Carvalho, C.C., Biofilms: Recent developments on an old battle (2007) Recent Pat Biotechnol, 1 (1), pp. 49-57; Costerton, J.W., Stewart, P.S., Greenberg, E.P., Bacterial biofilms: A common cause of persistent infections (1999) Science, 284 (5418), pp. 1318-1322. , DOI 10.1126/science.284.5418.1318; Willcox, M.D., Hume, E.B., Aliwarga, Y., Kumar, N., Cole, N., A novel cationic-peptide coating for the prevention of microbial colonization on contact lenses (2008) J Appl Microbiol, 105 (6), pp. 1817-1825; Lewis, K., Riddle of biofilm resistance (2001) Antimicrobial Agents and Chemotherapy, 45 (4), pp. 999-1007. , DOI 10.1128/AAC.45.4.999-1007.2001; Monteiro, D.R., Gorup, L.F., Takamiya, A.S., Ruvollo-Filho, A.C., De Camargo, E.R., Barbosa, D.B., The growing importance of materials that prevent microbial adhesion: Antimicrobial effect of medical devices containing silver (2009) Int J Antimicrob Agents, 34 (2), pp. 103-110; Gooderham, W.J., Bains, M., McPhee, J.B., Wiegand, I., Hancock, R.E., Induction by cationic antimicrobial peptides and involvement in intrinsic polymyxin and antimicrobial peptide resistance, biofilm formation, and swarming motility of PsrA in Pseudomonas aeruginosa (2008) J Bacteriol, 190 (16), pp. 5624-5634; Bagge, N., Schuster, M., Hentzer, M., Ciofu, O., Givskov, M., Greenberg, E.P., Hoiby, N., Pseudomonas aeruginosa Biofilms Exposed to Imipenem Exhibit Changes in Global Gene Expression and β-Lactamase and Alginate Production (2004) Antimicrobial Agents and Chemotherapy, 48 (4), pp. 1175-1187. , DOI 10.1128/AAC.48.4.1175-1187.2004; Ahmed, N.A., Petersen, F.C., Scheie, A.A., AI-2/LuxS is involved in increased biofilm formation by Streptococcus intermedius in the presence of antibiotics (2009) Antimicrob Agents Chemother, 53 (10), pp. 4258-4263; Hoffman, L.R., D'Argenio, D.A., MacCoss, M.J., Zhang, Z., Jones, R.A., Miller, S.I., Aminoglycoside antibiotics induce bacterial biofilm formation (2005) Nature, 436 (7054), pp. 1171-1175. , DOI 10.1038/nature03912; Harbers, G.M., Emoto, K., Greef, C., Metzger, S.W., Woodward, H.N., Mascali, J.J., Grainger, D.W., Lochhead, M.J., Functionalized poly(ethylene glycol)-based bioassay surface chemistry that facilitates bio-immobilization and inhibits nonspecific protein, bacterial, and mammalian cell adhesion (2007) Chemistry of Materials, 19 (18), pp. 4405-4414. , DOI 10.1021/cm070509u; Chapman, R.G., Ostuni, E., Liang, M.N., Meluleni, G., Kim, E., Yan, L., Pier, G., Whitesides, G.M., Polymeric thin films that resist the adsorption of proteins and the adhesion of bacteria (2001) Langmuir, 17 (4), pp. 1225-1233. , DOI 10.1021/la001222d; Goncalves, I.C., Martins, M.C., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) J Biomed Mater Res A, 89 (3), pp. 642-653; Chung, D., Papadakis, S.E., Yam, K.L., Evaluation of a polymer coating containing triclosan as the antimicrobial layer for packaging materials (2003) International Journal of Food Science and Technology, 38 (2), pp. 165-169. , DOI 10.1046/j.1365-2621.2003.00657.x; Leung, D., Spratt, D.A., Pratten, J., Gulabivala, K., Mordan, N.J., Young, A.M., Chlorhexidine-releasing methacrylate dental composite materials (2005) Biomaterials, 26 (34), pp. 7145-7153. , DOI 10.1016/j.biomaterials.2005.05.014, PII S0142961205003881; Ravikumar, T., Murata, H., Koepsel, R.R., Russell, A.J., Surface-active antifungal polyquaternary amine (2006) Biomacromolecules, 7 (10), pp. 2762-2769. , DOI 10.1021/bm060476w; Bach, A., Darby, D., Bottiger, B., Bohrer, H., Motsch, J., Martin, E., Retention of the antibiotic teicoplanin on a hydromer-coated central venous catheter to prevent bacterial colonization in postoperative surgical patients (1996) Intensive Care Medicine, 22 (10), pp. 1066-1069. , DOI 10.1007/s001340050214; Jose, B., Antoci Jr., V., Zeiger, A.R., Wickstrom, E., Hickok, N.J., Vancomycin covalently bonded to titanium beads kills Staphylococcus aureus (2005) Chemistry and Biology, 12 (9), pp. 1041-1048. , DOI 10.1016/j.chembiol.2005.06.013, PII S1074552105002309; Kilic, D., Agalar, C., Ozturk, E., Denkbas, E.B., Cime, A., Agalar, F., Antimicrobial activity of cefazolin-impregnated mesh grafts (2007) ANZ Journal of Surgery, 77 (4), pp. 256-260. , DOI 10.1111/j.1445-2197.2007.04029.x; Gallardo-Moreno, A.M., Pacha-Olivenza, M.A., Saldana, L., Perez-Giraldo, C., Bruque, J.M., Vilaboa, N., In vitro biocompatibility and bacterial adhesion of physico-chemically modified Ti6Al4V surface by means of UV irradiation (2009) Acta Biomater, 5 (1), pp. 181-192; Jansen, B., Kohnen, W., Prevention of biofilm formation by polymer modification (1995) Journal of Industrial Microbiology, 15 (4), pp. 391-396. , DOI 10.1007/BF01569996; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., Albumin and fibrinogen adsorption on Cibacron blue F3G-A immobilised onto PU-PHEMA (polyurethane-poly (hydroxyethylmethacrylate)) surfaces (2003) Journal of Biomaterials Science, Polymer Edition, 14 (5), pp. 439-455. , DOI 10.1163/156856203766652057; Zhang, F., Zhang, Z., Zhu, X., Kang, E.T., Neoh, K.G., Silk-functionalized titanium surfaces for enhancing osteoblast functions and reducing bacterial adhesion (2008) Biomaterials, 29 (36), pp. 4751-4759; Flemming, R.G., Capelli, C.C., Cooper, S.L., Proctor, R.A., Bacterial colonization of functionalized polyurethanes (2000) Biomaterials, 21 (3), pp. 273-281; Singla, A.K., Chawla, M., Chitosan: Some pharmaceutical and biological aspects - An update (2001) Journal of Pharmacy and Pharmacology, 53 (8), pp. 1047-1067. , DOI 10.1211/0022357011776441; Murata, H., Koepsel, R.R., Matyjaszewski, K., Russell, A.J., Permanent, non-leaching antibacterial surfaces-2: How high density cationic surfaces kill bacterial cells (2007) Biomaterials, 28 (32), pp. 4870-4879. , DOI 10.1016/j.biomaterials.2007.06.012, PII S0142961207004681; Aumsuwan, N., Danyus, R.C., Heinhorst, S., Urban, M.W., Attachment of ampicillin to expanded poly(tetrafluoroethylene): Surface reactions leading to inhibition of microbial growth (2008) Biomacromolecules, 9 (7), pp. 1712-1718; Cevher, E., Orhan, Z., Mulazimoglu, L., Sensoy, D., Alper, M., Yildiz, A., Characterization of biodegradable chitosan microspheres containing vancomycin and treatment of experimental osteomyelitis caused by methicillin-resistant Staphylococcus aureus with prepared microspheres (2006) Int J Pharm, 317 (2), pp. 127-135; Faber, C., Stallmann, H.P., Lyaruu, D.M., Joosten, U., Von Eiff, C., Van Nieuw Amerongen, A., Wuisman, P.I.J.M., Comparable efficacies of the antimicrobial peptide human lactoferrin 1-11 and gentamicin in a chronic methicillin-resistant Staphylococcus aureus osteomyelitis model (2005) Antimicrobial Agents and Chemotherapy, 49 (6), pp. 2438-2444. , DOI 10.1128/AAC.49.6.2438-2444.2005; Aumsuwan, N., Heinhorst, S., Urban, M.W., Antibacterial surfaces on expanded polytetrafluoroethylene; penicillin attachment (2007) Biomacromolecules, 8 (2), pp. 713-718. , DOI 10.1021/bm061050k; Palumbi, S.R., Humans as the world's greatest evolutionary force (2001) Science, 293 (5536), pp. 1786-1790. , DOI 10.1126/science.293.5536.1786; Andreu, D., Rivas, L., Animal antimicrobial peptides: An overview (1998) Biopolymers, 47 (6), pp. 415-433; Rivas, L., Luque-Ortega, J.R., Andreu, D., Amphibian antimicrobial peptides and Protozoa: Lessons from parasites (2009) Biochim Biophys Acta, 1788 (8), pp. 1570-1581; Gordon, Y.J., Romanowski, E.G., McDermott, A.M., Mini review: A review of antimicrobial peptides and their therapeutic potential as anti-infective drugs (2005) Current Eye Research, 30 (7), pp. 505-515. , DOI 10.1080/02713680590968637; Guani-Guerra, E., Santos-Mendoza, T., Lugo-Reyes, S.O., Teran, L.M., Antimicrobial peptides: General overview and clinical implications in human health and disease (2010) Clin Immunol, 135 (1), pp. 1-11; Perron, G.G., Zasloff, M., Bell, G., Experimental evolution of resistance to an antimicrobial peptide (2006) Proceedings of the Royal Society B: Biological Sciences, 273 (1583), pp. 251-256. , DOI 10.1098/rspb.2005.3301; Reddy, K.V.R., Yedery, R.D., Aranha, C., Antimicrobial peptides: Premises and promises (2004) International Journal of Antimicrobial Agents, 24 (6), pp. 536-547. , DOI 10.1016/j.ijantimicag.2004.09.005, PII S092485790400322X; Van 'T Hof, W., Veerman, E.C.I., Heimerhorst, E.J., Nieuw Amerongen, A.V., Antimicrobial peptides: Properties and applicability (2001) Biological Chemistry, 382 (4), pp. 597-619. , DOI 10.1515/BC.2001.072; Li, M., Cha, D.J., Lai, Y., Villaruz, A.E., Sturdevant, D.E., Otto, M., The antimicrobial peptide-sensing system aps of Staphylococcus aureus (2007) Molecular Microbiology, 66 (5), pp. 1136-1147. , DOI 10.1111/j.1365-2958.2007.05986.x; Li, M., Lai, Y., Villaruz, A.E., Cha, D.J., Sturdevant, D.E., Otto, M., Gram-positive three-component antimicrobial peptide-sensing system (2007) Proceedings of the National Academy of Sciences of the United States of America, 104 (22), pp. 9469-9474. , DOI 10.1073/pnas.0702159104; Otto, M., Bacterial sensing of antimicrobial peptides (2009) Contrib Microbiol, 16, pp. 136-149; Peschel, A., Vincent Collins, L., Staphylococcal resistance to antimicrobial peptides of mammalian and bacterial origin (2001) Peptides, 22 (10), pp. 1651-1659. , DOI 10.1016/S0196-9781(01)00500-9, PII S0196978101005009; Peschel, A., Jack, R.W., Otto, M., Collins, L.V., Staubitz, P., Nicholson, G., Kalbacher, H., Van Strijp, J.A.G., Staphylococcus aureus resistance to human defensins and evasion of neutrophil killing via the novel virulence factor MprF is based on modification of membrane lipids with L-lysine (2001) Journal of Experimental Medicine, 193 (9), pp. 1067-1076. , DOI 10.1084/jem.193.9.1067; Cao, M., Helmann, J.D., The Bacillus subtilis Extracytoplasmic-Function σ X Factor Regulates Modification of the Cell Envelope and Resistance to Cationic Antimicrobial Peptides (2004) Journal of Bacteriology, 186 (4), pp. 1136-1146. , DOI 10.1128/JB.186.4.1136-1146.2004; Clarke, S.R., Foster, S.J., IsdA protects Staphylococcus aureus against the bactericidal protease activity of apolactoferrin (2008) Infection and Immunity, 76 (4), pp. 1518-1526. , DOI 10.1128/IAI.01530-07; Vuong, C., Voyich, J.M., Fischer, E.R., Braughton, K.R., Whitney, A.R., DeLeo, F.R., Otto, M., Polysaccharide intercellular adhesin (PIA) protects Staphylococcus epidermidis against major components of the human innate immune system (2004) Cellular Microbiology, 6 (3), pp. 269-275. , DOI 10.1046/j.1462-5822.2004.00367.x; Zasloff, M., Antimicrobial peptides of multicellular organisms (2002) Nature, 415 (6870), pp. 389-395. , DOI 10.1038/415389a; Hancock, R.E.W., Peptide antibiotics (1997) Lancet, 349 (9049), pp. 418-422. , DOI 10.1016/S0140-6736(97)80051-7; Cho, W.-M., Joshi, B.P., Cho, H., Lee, K.-H., Design and synthesis of novel antibacterial peptide-resin conjugates (2007) Bioorganic and Medicinal Chemistry Letters, 17 (21), pp. 5772-5776. , DOI 10.1016/j.bmcl.2007.08.056, PII S0960894X0701013X; Statz, A.R., Park, J.P., Chongsiriwatana, N.P., Barron, A.E., Messersmith, P.B., Surface-immobilised antimicrobial peptoids (2008) Biofouling, 24 (6), pp. 439-448; Deslouches, B., Gonzalez, I.A., DeAlmeida, D., Islam, K., Steele, C., Montelaro, R.C., Mietzner, T.A., De novo-derived cationic antimicrobial peptide activity in a murine model of Pseudomonas aeruginosa bacteraemia (2007) Journal of Antimicrobial Chemotherapy, 60 (3), pp. 669-672. , DOI 10.1093/jac/dkm253; Novak, K.F., Diamond, W.J., Kirakodu, S., Peyyala, R., Anderson, K.W., Montelaro, R.C., Mietzner, T.A., Efficacy of the de novo-derived antimicrobial peptide WLBU2 against oral bacteria (2007) Antimicrobial Agents and Chemotherapy, 51 (5), pp. 1837-1839. , DOI 10.1128/AAC.00924-06; Deslouches, B., Islam, K., Craigo, J.K., Paranjape, S.M., Montelaro, R.C., Mietzner, T.A., Activity of the de novo engineered antimicrobial peptide WLBU2 against Pseudomonas aeruginosa in human serum and whole blood: Implications for systemic applications (2005) Antimicrobial Agents and Chemotherapy, 49 (8), pp. 3208-3216. , DOI 10.1128/AAC.49.8.3208-3216.2005; Deslouches, B., Phadke, S.M., Lazarevic, V., Cascio, M., Islam, K., Montelaro, R.C., Mietzner, T.A., De novo generation of cationic antimicrobial peptides: Influence of length and tryptophan substitution on antimicrobial activity (2005) Antimicrobial Agents and Chemotherapy, 49 (1), pp. 316-322. , DOI 10.1128/AAC.49.1.316-322.2005; Levin, M., Quint, P.A., Goldstein, B., Barton, P., Bradley, J.S., Shemie, S.D., Recombinant bactericidal/permeability-increasing protein (rBPI21) as adjunctive treatment for children with severe meningococcal sepsis: A randomised trial. rBPI21 Meningococcal Sepsis Study Group (2000) Lancet, 356 (9234), pp. 961-967; Giroir, B.P., Scannon, P.J., Levin, M., Bactericidal/permeability-increasing protein-lessons learned from the phase III, randomized, clinical trial of rBPI21 for adjunctive treatment of children with severe meningococcemia (2001) Crit Care Med, 29 (7 SUPPL.), pp. 130-135; Brogden, K.A., Antimicrobial peptides: Pore formers or metabolic inhibitors in bacteria? (2005) Nature Reviews Microbiology, 3 (3), pp. 238-250. , DOI 10.1038/nrmicro1098; Bastos, M., Bai, G., Gomes, P., Andreu, D., Goormaghtigh, E., Prieto, M., Energetics and partition of two cecropin-melittin hybrid peptides to model membranes of different composition (2008) Biophys J, 94 (6), pp. 2128-2141; Melo, M.N., Ferre, R., Castanho, M.A., Antimicrobial peptides: Linking partition, activity and high membrane-bound concentrations (2009) Nat Rev Microbiol, 7 (3), pp. 245-250; Haynie, S.L., Crum, G.A., Doele, B.A., Antimicrobial activities of amphiphilic peptides covalently bonded to a water-insoluble resin (1995) Antimicrob Agents Chemother, 39 (2), pp. 301-307; Humblot, V., Yala, J.F., Thebault, P., Boukerma, K., Hequet, A., Berjeaud, J.M., The antibacterial activity of Magainin i immobilized onto mixed thiols self-assembled monolayers (2009) Biomaterials, 30 (21), pp. 3503-3512; Bagheri, M., Beyermann, M., Dathe, M., Immobilization reduces the activity of surface-bound cationic antimicrobial peptides with no influence upon the activity spectrum (2009) Antimicrob Agents Chemother, 53 (3), pp. 1132-1141; Gabriel, M., Nazmi, K., Veerman, E.C., Nieuw Amerongen, A.V., Zentner, A., Preparation of LL-37-grafted titanium surfaces with bactericidal activity (2006) Bioconj Chem, 17 (2), pp. 548-550; Hilpert, K., Elliott, M., Jenssen, H., Kindrachuk, J., Fjell, C.D., Korner, J., Screening and characterization of surface-tethered cationic peptides for antimicrobial activity (2009) Chem Biol, 16 (1), pp. 58-69; Batista, M.K.S., Gallemi, M., Adeva, A., Gomes, C.A.R., Gomes, P., Facile regioselective synthesis of a novel chitosan-pexiganan conjugate with potential interest for the treatment of infected skin lesions (2009) Synthetic Commun, 39 (7), pp. 1228-1240; Venter, J.C., Immobilized and insolubilized drugs, hormones, and neurotransmitters: Properties, mechanisms of action and applications (1982) Pharmacological Reviews, 34 (2), pp. 153-187; Endo, Y., Tani, T., Kodama, M., Antimicrobial activity of tertiary amine covalently bonded to a polystyrene fiber (1987) Appl Environ Microbiol, 53 (9), pp. 2050-2055; Chuang, H.F., Shukla, A., Loose, C.R., Hammond-Cunningham, P.T., Stephanopoulos, G., (2009) Structures Including Antimicrobial Peptides, , United States; Chen, R., Cole, N., Willcox, M.D., Park, J., Rasul, R., Carter, E., Synthesis, characterization and in vitro activity of a surface-attached antimicrobial cationic peptide (2009) Biofouling, 25 (6), pp. 517-524; Steven, M.D., Hotchkiss, J.H., Covalent immobilization of an antimicrobial peptide on poly(ethylene) film (2008) J Appl Polym Sci, 110 (5), pp. 2665-2670; Appendini, P., Hotchkiss, J.H., Surface modification of poly(styrene) by the attachment of an antimicrobial peptide (2001) J Appl Polym Sci, 81 (3), pp. 609-616; Fields, G.B., Noble, R.L., Solid phase peptide synthesis utilizing 9-fluorenylmethoxycarbonyl amino acids (1990) International Journal of Peptide and Protein Research, 35 (3), pp. 161-214; Rostovtsev, V.V., Green, L.G., Fokin, V.V., Sharpless, K.B., A stepwise huisgen cycloaddition process: Copper(I)-catalyzed regioselective "ligation" of azides and terminal alkynes (2002) Angewandte Chemie - International Edition, 41 (14), pp. 2596-2599. , DOI 10.1002/1521-3773(20020715)41: 14<2596::AID-ANIE2596>3.0.CO;2-4; Abad, J.M., Velez, M., Santamaria, C., Guisan, J.M., Matheus, P.R., Vazquez, L., Gazaryan, I., Fernandez, V.M., Immobilization of peroxidase glycoprotein on gold electrodes modified with mixed epoxy-boronic acid monolayers (2002) Journal of the American Chemical Society, 124 (43), pp. 12845-12853. , DOI 10.1021/ja026658p; Lee, M.-R., Shin, I., Fabrication of chemical microarrays by efficient immobilization of hydrazide-linked substances on epoxide-coated glass surfaces (2005) Angewandte Chemie - International Edition, 44 (19), pp. 2881-2884. , DOI 10.1002/anie.200462720; Hudalla, G.A., Murphy, W.L., Immobilization of peptides with distinct biological activities onto stem cell culture substrates using orthogonal chemistries (2010) Langmuir, 26 (9), pp. 6449-6456; Cole, N., Hume, E.B., Vijay, A.K., Sankaridurg, P., Kumar, N., Willcox, M.D., In vivo performance of melimine as an antimicrobial coating for contact lenses in models of CLARE and CLPU (2010) Invest Ophthalmol Vis Sci, 51 (1), pp. 390-395
Keywords: Amino Acid Sequence; amoxicillin; ampicillin; Animals; antibiotic agent; antibiotic resistance; Antimicrobial Cationic Peptides; Antimicrobial peptides; Bacteria (microorganisms); Bacterial adhesion; bacterial survival; Biocompatible Materials; biofilm; Biofilms; biomaterial; carbenicillin; cefazolin; Coated Materials, Biocompatible; Cytotoxicity; drug activity; drug half life; drug solubility; drug stability; drug targeting; gentamicin; human; Humans; Immobilized Proteins; Molecular Sequence Data; mouth inflammation; Nanostructured surfaces; nonhuman; penicillin G; polypeptide antibiotic agent; priority journal; review; sepsis; skin infection; soft tissue infection; Surface functionalization; Surface Properties; teicoplanin; tobramycin; vancomycin

The effect of slurry preparation methods on biaxial flexural strength of dental porcelain - Pelaez-Vargas, A.; Dussan, J.A.; Restrepo-Tamayo, L.F.; Paucar, C.; Ferreira, J.A.; Monteiro, F.J. (Journal of Prosthetic DentistryJ. Prosthet. Dent., 2011)
Statement of problem. One-step and incremental mixing procedures are currently used to produce dental ceramic pastes. In the ceramic industry, high quality is obtained using one-step mixing, but in dentistry, the best method has not been yet determined. Purpose. The purpose of this study is to evaluate the effects of 2 mixing techniques on the biaxial flexural strength and microstructure of dental porcelain. Material and methods. Feldspathic porcelain discs (2 × 15 mm in diameter) were produced and divided according to the ceramic paste preparation method, powder-liquid incremental mixing group (n=50) or one-step mixing, as a control group (n=50). Specimens were tested for biaxial flexural strength and characterized using porosimetry, relative humidity, SEM/EDS, XRD, and FT-IR analyses. Statistical analysis was conducted using Weibull statistics. The Weibull modulus, characteristic strength and relative humidity were compared between groups, using Student's t-test and Mann-Whitney U test (α=.05). Results. The powder-liquid incremental mixing group showed significantly higher values (SD) of Weibull modulus (6.74 (0.70), P<.001) and characteristic strength (79.87 (2.01) MPa, P<.001) when compared to the one-step mixing group (4.94 (0.94) and 75.95 (2.61) MPa). Significantly lower mean (SD) relative humidity values (P=.009) were found for powder-liquid incremental mixing group (20% (0.5%)) compared to one-step mixing group (22% (1%)). XRD spectra showed that the one-step mixing group produced higher amounts of the amorphous phase. Conclusions. Specimens produced by the incremental mixing technique showed higher biaxial flexural strength than one-step mixing. © 2011 The Editorial Council of the Journal of Prosthetic Dentistry.
Keywords: article; chemistry; comparative study; Complex Mixtures; Crowns; dental care; Dental Porcelain; Dental Prosthesis Design; Dental Stress Analysis; Dental Veneers; denture; drug mixture; evaluation; materials testing; pliability; tooth crown; tooth prosthesis

Friction and wear behaviour of bacterial cellulose against articular cartilage - Lopes, J.L.; Machado, J.M.; Castanheira, L.; Granja, P.L.; Gama, F.M.; Dourado, F.; Gomes, J.R. (WearWear, 2011)
Bacterial cellulose (BC) is a natural and biocompatible material with unique properties, such as high water holding capacity, ultra-fine fibre network and high strength that makes it an attractive material for the repair of articular cartilage lesions. However, data on the tribological properties of BC is very scarce, particularly if natural articular cartilage is involved in the contact. In this work, unmodified BC pellicles were grown from Gluconacetobacter xylinus in order to be used as tribological samples against bovine articular cartilage (BAC) in the presence of phosphate buffered saline (PBS). The tribological assessment of the sliding pairs was accomplished using reciprocating pin-on-flat tests at 37°C. The reciprocating sliding frequency and stroke length were kept constant at 1Hz and 8mm, respectively. Contact pressures ranging from 0.80 to 2.40MPa were applied. The friction coefficient evolution was continuously monitored during the tests and the release of total carbohydrates into the lubricating solution was followed by means of the phenol-H 2SO 4 method as an attempt to evaluate wear losses. The morphology of worn surfaces was characterized by SEM/EDS and the main wear mechanisms were identified. Low friction coefficient values (∼0.05) combined with the preservation of the mating surfaces (BC and BAC) indicate the potential of BC to be used as artificial cartilage for articular joints. © 2011 Elsevier B.V.
Keywords: Articular cartilage; Articular cartilages; Articular joints; Artificial cartilages; Bacterial cellulose; Bacteriology; Biocompatible Materials; Biological materials; Biotribology; Bovine articular cartilage; Carbohydrates; Cartilage; Cellulose; Contact pressures; Fibre network; Friction; Friction and wear; Friction coefficients; Gluconacetobacter xylinus; High strength; High water; Low friction coefficients; Mating surfaces; Phenols; Phosphate-buffered salines; Pin-on-flat; Reciprocating sliding; SEM/EDS; Stroke length; Total carbohydrates; Tribological properties; Tribology; Wear; Wear loss; Wear mechanisms; Worn surface

Gene delivery into mesenchymal stem cells: A biomimetic approach using rgd nanoclusters based on poly(amidoamine) dendrimers - Pandita, D.; Santos, J.L.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (BiomacromoleculesBiomacromolecules, 2011)
Poly(amidoamine) dendrimers (generations 5 and 6) with amine termini were conjugated with peptides containing the arginine-glycine-aspartic acid (RGD) sequence having in view their application as gene delivery vectors. The idea behind the work was to take advantage of the cationic nature of dendrimers and of the integrin targeting capabilities of the RGD motif to improve gene delivery. Dendrimers were used as scaffolds for RGD clustering and, by controlling the number of peptides (4, 8, and 16) linked to each dendrimer, it was possible to evaluate the effect of RGD density on the gene delivery process. The new vectors were characterized in respect to their ability to neutralize and compact plasmid DNA (pDNA). The complexes formed by the vectors and pDNA were studied concerning their size, zeta potential, capacity of being internalized by cells and ability of transferring genes. Transfection efficiency was analyzed, first, by using a pDNA encoding for Enhanced Green Fluorescent Protein and Firefly Luciferase and, second, by using a pDNA encoding for Bone Morphogenetic Protein-2. Gene expression in mesenchymal stem cells was enhanced using the new vectors in comparison to native dendrimers and was shown to be dependent on the electrostatic interaction established between the dendrimer moiety and the cell surface, as well as on the RGD density of nanoclusters. The use of dendrimer scaffolds for RGD cluster formation is a new approach that can be extended beyond gene delivery applications, whenever RGD clustering is important for modulating cellular responses. © 2011 American Chemical Society.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm1012647PubMed ID: 21210673Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM-Centro de Química da Madeira, MMRG, Universidade da Madeira, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: arginylglycylaspartic acid, 99896-85-2; firefly luciferase, 61970-00-1; Dendrimers; Oligopeptides; Poly(amidoamine); Polyamines; arginyl-glycyl-aspartic acid, 99896-85-2References: Pierschbacher, M.D., Ruoslahti, E., (1984) Nature, 309, pp. 30-33;Ruoslahti, E., (1996) Annu. Rev. Cell Dev. Biol., 12, pp. 697-715; Schaffn, P., Dard, M.M., (2003) Cell. Mol. Life Sci., 60, pp. 119-132; Arosio, D., Manzoni, L., Araldi, E.M.V., Caprini, A., Monferini, E., Scolastico, C., (2009) Bioconjugate Chem., 20, pp. 1611-1617; Cai, W., Chen, X., (2008) Nat. Protoc., 3, pp. 89-96; Cai, W., Wu, Y., Chen, K., Cao, Q., Tice, D.A., Chen, X., (2006) Cancer Res., 66, pp. 9673-9681; Gaillard, C., Cellot, G., Li, S., Toma, F.M., Dumortier, H., Spalluto, G., Cacciari, B., Bianco, A., (2009) Adv. Mater., 21, pp. 1-6; Green, J.J., Chiu, E., Leshchiner, E.S., Shi, J., Langer, R., Anderson, D.G., (2007) Nano Lett., 7, pp. 874-879; Hwang, D.S., Sim, S.B., Cha, H.J., (2007) Biomaterials, 28, pp. 4039-4046; Irvine, D.J., Mayes, A.M., Griffith, L.G., (2001) Biomacromolecules, 2, pp. 85-94; Kong, H.J., Hsiong, S., Mooney, D.J., (2007) Nano Lett., 7, pp. 161-166; Lesniak, W.G., Kariapper, M.S., Nair, B.M., Tan, W., Hutson, A., Balogh, L.P., Khan, M.K., (2007) Bioconjugate Chem., 18, pp. 1148-1154; Ng, Q.K., Sutton, M.K., Soonsawad, P., Xing, L., Cheng, H., Segura, T., (2009) Mol. Ther., 17, pp. 828-836; Suk, J.S., Suh, J., Choy, K., Lai, S.K., Fu, J., Hanes, J., (2006) Biomaterials, 27, pp. 5143-5150; Sun, Y.X., Zeng, X., Meng, Q.F., Zhang, X.Z., Cheng, S.X., Zhuo, R.X., (2008) Biomaterials, 29, pp. 4356-4365; Yang, H., Kao, W.J., (2007) Int. J. Nanomed., 2, pp. 89-99; Yoshimoto, M., Ogawa, K., Washiyama, K., Shikano, N., Mori, H., Amano, R., Kawai, K., (2008) Int. J. Cancer, 123, pp. 709-715; Bidarra, S.J., Barrias, C.C., Barbosa, M.A., Soares, R., Granja, P.L., (2010) Biomacromolecules, 11, pp. 1956-1964; Grellier, M., Granja, P.L., Fricain, J.-C., Bidarra, S.J., Renard, M., Bareille, R., Bourget, C., Barbosa, M.A., (2009) Biomaterials, 30, pp. 3271-8; Evangelista, M.B., Hsiong, S., Fernandes, R., Sampaio, P., Kong, H.J., Barrias, C.C., Salema, R., Granja, P.L., (2007) Biomaterials, 28, pp. 3644-55; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., (2001) J. Dental Res., 80, pp. 2025-9; Rowley, J.A., Madlambayan, G., Mooney, D.J., (1999) Biomaterials, 20, pp. 45-53; Hynes, R.O., (2002) Cell, 110, pp. 673-687; Qin, J., Vinogradova, O., Plow, E.F., (2004) PLoS Biol., 2, pp. e169; Medina-Kauwe, L.K., (2003) Adv. Drug Delivery Rev., 55, pp. 1485-1496; Stewart, P.L., Chiu, C.Y., Huang, S., Muir, T., Zhao, Y., Chait, B., Mathias, P., Nemerow, G.R., (1997) EMBO J., 16, pp. 1189-1198; Dufès, C., Uchegbu, I.F., Schätzlein, A.G., (2005) Adv. Drug Delivery Rev., 57, pp. 2177-2202; Mintzer, M.A., Simanek, E.E., (2009) Chem. Rev., 109, pp. 259-302; Smith, D.K., (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Svenson, S., Tomalia, D.A., (2005) Adv. Drug Delivery Rev., 57, pp. 2106-2129; Dennig, J., Duncan, E., (2002) J. Biotechnol., 90, pp. 339-347; Sokolova, V.V., Radtke, I., Heumann, R., Epple, M., (2006) Biomaterials, 27, pp. 3147-3153; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker Jr., J.R., (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pêgo, A.P., Granja, P.L., Tomás, H., (2009) J. Controlled Release, 134, pp. 141-148; Prockop, D.J., (2009) Mol. Ther., 17, pp. 939-946; Väänänen, H.K., (2005) Ann. Med., 37, pp. 469-479; Gronthos, S., Simmons, P.J., Graves, S.E., Robey, P.G., (2001) Bone, 28, pp. 174-181; Snyder, S.L., Sobocinski, P.Z., (1975) Anal. Biochem., 64, pp. 284-288; Haensler, J., Szoka Jr., F.C., (1993) Bioconjugate Chem, 4, pp. 372-379; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Anal. Biochem., 150, pp. 76-85; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., (2003) Toxicol. Sci., 72, pp. 122-129; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., (2006) Biomaterials, 27, pp. 1387-1398; Zhang, S., Li, J., Lykotrafitis, G., Bao, G., Suresh, S., (2009) Adv. Mater., 21, pp. 419-424; Tang, M.X., Szoka, F.C., (1997) Gene Ther., 4, pp. 823-32; Santos, J.L., Pandita, D., Rodrigues, J., Pêgo, A.P., Granja, P.L., Balian, G., Tomás, H., (2010) Mol. Pharm., 7, pp. 763-774; Santos, J.L., Oliveira, H., Pandita, D., Rodrigues, J., Pêgo, A.P., Granja, P.L., Tomás, H., (2010) J. Controlled Release, 144, pp. 55-64; Kunath, K., Merdan, T., Hegener, O., Häberlein, H., Kissel, T., (2003) J. Gene Med., 5, pp. 588-599; Lechardeur, D., Verkman, A.S., Lukacs, G.L., (2005) Adv. Drug Delivery Rev., 57, pp. 755-767; Ryoo, H.M., Lee, M.H., Kim, Y.J., (2006) Gene, 366, pp. 51-57
Keywords: Amino Acid Sequence; Amino acids; animal cell; animal experiment; Animals; Arginine-glycine-aspartic acids; arginylglycylaspartic acid; article; Biomimetics; bone morphogenetic protein 2; Bone morphogenetic protein-2; Cell culture; Cell membranes; cell surface; Cell surfaces; cell survival; Cellular response; Cluster formations; Complexation; controlled study; dendrimer; Dendrimers; Electrostatic interactions; electrostatic precipitation; Encoding (symbols); Enhanced green fluorescent protein; Firefly luciferase; Functional polymers; Gene delivery; Gene delivery vectors; gene expression; gene targeting; Gene therapy; Gene transfer; Gene Transfer Techniques; gene vector; integrin; Integrins; male; Mesenchymal stem cell; Mesenchymal Stem Cells; Molecular Structure; Nanoclusters; Nanostructures; New approaches; nonhuman; Oligopeptides; Organic acids; Peptides; plasmid DNA; Plasmid DNA (pDNA); polyamidoamine; Polyamidoamine dendrimers; Polyamines; priority journal; rat; Rats; Rats, Wistar; RGD motif; Scaffolds; Stem cells; Structure-Activity Relationship; Targeting capability; Transfection efficiency; Vectors; Zeta potential

Interactions of leukocytes and platelets with poly(lysine/leucine) immobilized on tetraethylene glycol-terminated self-assembled monolayers - Martins, M.C.L.; Ochoa-Mendes, V.; Ferreira, G.; Barbosa, J.N.; Curtin, S.A.; Ratner, B.D.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2011)
Surfaces that bind heparin are important for biomaterials for blood deheparinization. In our recent work it was demonstrated that a polypeptide composed of l-lysine and l-leucine (pKL), after immobilization onto tetra(ethylene glycol) terminated self-assembled monolayers (EG4-SAMs), can bind heparin from blood plasma in a selective, concentration-dependent way. During this work the effect of this peptide on platelet adhesion and activation and leukocyte adhesion was studied. The surface charge of these nanostructured surfaces was evaluated in order to correlate the effect of positively charged amine groups and hydrophobic methyl groups on the behavior of platelets and leukocyte adhesion. The results demonstrated that the presence of pKL decreased leukocyte adhesion to EG4-SAMs at all concentrations used. This effect is even more pronounced when surfaces were pre-immersed in heparinized plasma. In contrast, there is an increase in platelet adhesion and activation with increased percentage immobilized pKL. This effect is enhanced when surfaces were pre-immersed in heparinized plasma. However, adsorbed pKL in very low amounts does not induce platelet adhesion and activation compared with EG4, even when pre-immersed in plasma. Since only low pKL amounts are necessary to induce heparin selectivity, these results are promising for the development of heparin-binding biomaterials for blood deheparinization. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2011.01.013PubMed ID: 21237292Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; leucine, 61-90-5, 7005-03-0; polylysine, 25104-18-1, 25988-63-0, 33960-24-6, 38000-06-5, 73565-56-7; Ethylene Glycol, 107-21-1; Imidazoles; Immobilized Proteins; N,N-carbonyldiimidazole, 530-62-1; Polyethylene Glycols; Polylysine, 25104-18-1; ProteinsReferences: Dailey, J., (1998) Blood, , 2nd ed. Ipswich (MA, USA): Medical Consulting Group;Section V: Chronic intermittent haemodialysis and prevention of clotting in the extracorporal system (2002) Nephrol Dial Transplant, 17 (SUPPL. 7), pp. 63-71. , European Best Practice Guidelines Working Group; Martins, M.C., Curtin, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88, pp. 162-173; Love, J.C., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chemical Reviews, 105 (4), pp. 1103-1169. , DOI 10.1021/cr0300789; Cardin, A.D., Weintraub, H.J.R., Molecular modeling of protein-glycosaminoglycan interactions (1989) Arteriosclerosis, 9 (1), pp. 21-32; Prime, K.L., Whitesides, G.M., Adsorption of proteins onto surfaces containing end-attached oligo(ethylene oxide) - A model system using self-assembled monolayers (1993) J Am Chem Soc, 115, pp. 10714-10721; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) Journal of Biomedical Materials Research - Part A, 67 (1), pp. 158-171; Werner, C., Konig, U., Augsburg, A., Arnhold, C., Korber, H., Zimmermann, R., Jacobasch, H.-J., Electrokinetic surface characterization of biomedical polymers - A survey (1999) Colloids and Surfaces A: Physicochemical and Engineering Aspects, 159 (2-3), pp. 519-529. , DOI 10.1016/S0927-7757(99)00290-3, PII S0927775799002903; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.-G., Glutardialdehyde induced fluorescence technique (GIFT): A new method for the imaging of platelet adhesion on biomaterials (2000) Journal of Biomedical Materials Research, 52 (2), pp. 374-381. , DOI 10.1002/1097-4636(200011)52:2<374::AID-JBM18>3.0.CO;2-Z; Chan, Y.H.M., Schweiss, R., Werner, C., Grunze, M., Electrokinetic characterization of oligo- and poly(ethylene glycol)-terminated self-assembled monolayers on gold and glass surfaces (2003) Langmuir, 19, pp. 7380-7385; Schweiss, R., Welzel, P.B., Werner, C., Knoll, W., Dissociation of surface functional groups and preferential adsorption of ions on self-assembled monolayers assessed by streaming potential and streaming current measurements (2001) Langmuir, 17 (14), pp. 4304-4311. , DOI 10.1021/la001741g; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27 (31), pp. 5357-5367. , DOI 10.1016/j.biomaterials.2006.06.010, PII S0142961206005515; Goncalves, I.C., Martins, M.C., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) J Biomed Mater Res, 89 A, pp. 642-653; Prime, K.L., Whitesides, G.M., Self-assembled organic monolayers: Model systems for studying adsorption of proteins at surfaces (1991) Science, 252 (5009), pp. 1164-1167; Mrksich, M., Using self-assembled monolayers to model the extracellular matrix (2009) Acta Biomater, 5, pp. 832-841; Sagnella, S., Mai-Ngam, K., Chitosan based surfactant polymers designed to improve blood compatibility on biomaterials (2005) Colloids Surf B Biointerfaces, 42, pp. 147-155; Chuang, W.H., Lin, J.C., Surface characterization and platelet adhesion studies for the mixed self-assembled monolayers with amine and carboxylic acid terminated functionalities (2007) J Biomed Mater Res A, 82, pp. 820-830; Chen, S., Yu, F., Yu, Q., He, Y., Jiang, S., Strong resistance of a thin crystalline layer of balanced charged groups to protein adsorption (2006) Langmuir, 22 (19), pp. 8186-8191. , DOI 10.1021/la061012m; Chen, S.F., Jiang, S.Y., A new avenue to nonfouling materials (2008) Adv Mater, 20, p. 335; Li, D., Chen, H., Glenn McClung, W., Brash, J.L., Lysine-PEG-modified polyurethane as a fibrinolytic surface. effect of PEG chain length on protein interactions, platelet interactions and clot lysis (2009) Acta Biomater, 5, pp. 1864-1871; Tsai, W.-B., Grunkemeier, J.M., Horbett, T.A., Variations in the ability of adsorbed fibrinogen to mediate platelet adhesion to polystyrene-based materials: A multivariate statistical analysis of antibody binding to the platelet binding sites of fibrinogen (2003) Journal of Biomedical Materials Research - Part A, 67 (4), pp. 1255-1268; Weisel, J.W., Nagaswami, C., Vilaire, G., Bennett, J.S., Examination of the platelet membrane glycoprotein IIb-IIIa complex and its interaction with fibrinogen and other ligands by electron microscopy (1992) J Biol Chem, 267 (23), pp. 16637-16643; Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: Roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25 (26), pp. 5681-5703. , DOI 10.1016/j.biomaterials.2004.01.023, PII S0142961204000687; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polym Ed, 4, pp. 591-599; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) Journal of the American Chemical Society, 120 (14), pp. 3464-3473. , DOI 10.1021/ja970819l; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) Journal of Colloid and Interface Science, 185 (1), pp. 94-103. , DOI 10.1006/jcis.1996.4586; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (2000) Journal of Biomedical Materials Research, 49 (4), pp. 435-447. , DOI 10.1002/(SICI)1097-4636(20000315)49:4<435::AID-JBM2>3.0.CO;2-Y; Werthen, M., Sellborn, A., Kalltorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) Journal of Biomedical Materials Research, 50 (3), pp. 291-301. , DOI 10.1002/(SICI)1097-4636(20000605)50:3<291::AID-JBM2>3.0.CO;2-1; Barbosa, J.N., Martins, M.C.L., Freitas, S.C., Goncalves, I.C., Aguas, A.P., Barbosa, M.A., Adhesion of human leucocytes on mixtures of hydroxyl- and methyl-terminated self-assembled monolayers: Effect of blood protein adsorption (2010) J Biomed Mater Res, 93 A, pp. 12-19; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Toda, M., Kitazawa, T., Hirata, I., Hirano, Y., Iwata, H., Complement activation on surfaces carrying amino groups (2008) Biomaterials, 29 (4), pp. 407-417. , DOI 10.1016/j.biomaterials.2007.10.005, PII S014296120700796X
Keywords: article; Blood Platelets; Cell Communication; Cell Shape; Ethylene Glycol; heparin; heparin binding protein; Humans; hydrophobicity; Imidazoles; Immobilized Proteins; leucine; leukocyte; leukocyte adherence; Leukocytes; methyl group; nanomaterial; plasma; Platelet Adhesiveness; Platelets; Polyethylene Glycols; polylysine; polypeptide; priority journal; Proteins; self assembled monolayer; Self-assembled monolayers; static electricity; Surface charge; Surface Properties; Tetra; thrombocyte; thrombocyte adhesion

Isotropic micropatterned silica coatings on zirconia induce guided cell growth for dental implants - Pelaez-Vargas, A.; Gallego-Perez, D.; Magallanes-Perdomo, M.; Fernandes, M.H.; Hansford, D.J.; De Aza, A.H.; Pena, P.; Monteiro, F.J. (Dental MaterialsDent. Mater., 2011)
Titanium implants are the gold standard in dentistry; however, problems such as gingival tarnishing and peri-implantitis have been reported. For zirconia to become a competitive alternative dental implant material, surface modification techniques that induce guided tissue growth must be developed. Objectives: To develop alternative surface modification techniques to promote guided tissue regeneration on zirconia materials, for applications in dental implantology. Methods: A methodology that combined soft lithography and sol-gel chemistry was used to obtain isotropic micropatterned silica coatings on yttria-stabilized zirconia substrates. The materials were characterized via chemical, structural, surface morphology approaches. In vitro biological behavior was evaluated in terms of early adhesion and viability/metabolic activity of human osteoblast-like cells. Statistical analysis was conducted using one-way ANOVA/Tukey HSD post hoc test. Results: Isotropic micropatterned silica coatings on yttria-stabilized zirconia substrates were obtained using a combined approach based on sol-gel technology and soft lithography. Micropatterned silica surfaces exhibited a biocompatible behavior, and modulated cell responses (i.e. inducing early alignment of osteoblast-like cells). After 7 d of culture, the cells fully covered the top surfaces of pillar microstructured silica films. Significance: The micropatterned silica films on zirconia showed a biocompatible response, and were capable of inducing guided osteoblastic cell adhesion, spreading and propagation. The results herein presented suggest that surface-modified ceramic implants via soft lithography and sol-gel chemistry could potentially be used to guide periodontal tissue regeneration, thus promoting tight tissue apposition, and avoiding gingival retraction and peri-implantitis. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: DEMAEdoi: 10.1016/j.dental.2011.02.014Language of Original Document: EnglishCorrespondence Address: Pelaez-Vargas, A.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: alejopv@ineb.up.ptChemicals/CAS: resazurin, 550-82-3; silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; yttrium, 7440-65-5; zirconium, 14940-68-2, 7440-67-7; Ceramics; Coated Materials, Biocompatible; Dental Implants; Dental Materials; Indicators and Reagents; Oxazines; Silicon Dioxide, 7631-86-9; Xanthenes; Yttrium, 7440-65-5; Zirconium, 7440-67-7; resazurin, 550-82-3; yttria stabilized tetragonal zirconiaReferences: Kasemo, B., Biocompatibility of titanium implants: Surface science aspects (1983) J Prosthet Dent, 49, pp. 832-837;Egusa, H., Ko, N., Shimazu, T., Yatani, H., Suspected association of an allergic reaction with titanium dental implants: A clinical report (2008) J Prosthet Dent, 100, pp. 344-347; Tschernitschek, H., Borchers, L., Geurtsen, W., Nonalloyed titanium as a bioinert metal - A review (2005) Quintessence International, 36 (7), pp. 523-530; Oliva, J., Oliva, X., Oliva, J., One-year follow-up of first consecutive 100 zirconia dental implants in human: A comparison of 2 different rough surfaces (2007) Int J Oral Maxillofac Implants, 22, pp. 430-435; Johansson, C.B., Hansson, H.A., Albrektsson, T., Qualitative interfacial study between bone and tantalum, niobium or commercially pure titanium (1990) Biomaterials, 11, pp. 277-280; De Wijs, F.L., Van Dongen, R.C., De Lange, G.L., De Putter, C., Front tooth replacement with Tubingen (Frialit) implants (1994) J Oral Rehabil, 21, pp. 11-26; Albrektsson, T., Lekholm, U., Osseointegration: Current state of the art (1989) Dent Clin North Am, 33, pp. 537-554; Albrektsson, T., Sennerby, L., State of the art in oral implants (1991) J Clin Periodontol, 18, pp. 474-481; Albrektsson, T., Sennerby, L., Wennerberg, A., State of the art of oral implants (2008) Periodontol 2000, 47, pp. 15-26; Sennerby, L., Dental implants: Matters of course and controversies (2008) Periodontol 2000, 47, pp. 9-14; Leblebicioglu, B., Rawal, S., Mariotti, A., A review of the functional and esthetic requirements for dental implants (2007) J Am Dent Assoc, 138, pp. 321-329; Chevalier, J., What future for zirconia as a biomaterial? (2006) Biomaterials, 27 (4), pp. 535-543. , DOI 10.1016/j.biomaterials.2005.07.034, PII S0142961205007039; Hochman, N., Zalkind, M., New all-ceramic indirect post-and-core system (1999) J Prosthet Dent, 81, pp. 625-629; Malmstrom, J., Slotte, C., Adolfsson, E., Norderyd, O., Thomsen, P., Bone response to free form-fabricated hydroxyapatite and zirconia scaffolds: A histological study in the human maxilla (2009) Clin Oral Implants Res, 20, pp. 379-385; Manicone, P.F., Rossi Iommetti, P., Raffaelli, L., An overview of zirconia ceramics: Basic properties and clinical applications (2007) J Dent, 35, pp. 819-826; Kim, H.-W., Kim, H.-E., Salih, V., Knowles, J.C., Dissolution control and cellular responses of calcium phosphate coatings on zirconia porous scaffold (2004) Journal of Biomedical Materials Research - Part A, 68 (3), pp. 522-530; Kim, H.W., Shin, S.Y., Kim, H.E., Lee, Y.M., Chung, C.P., Lee, H.H., Bone formation on the apatite-coated zirconia porous scaffolds within a rabbit calvarial defect (2008) J Biomater Appl, 22, pp. 485-504; Akagawa, Y., Hosokawa, R., Sato, Y., Kamayama, K., Comparison between freestanding and tooth-connected partially stabilized zirconia implants after two years' function in monkeys: A clinical and histologic study (1998) J Prosthet Dent, 80, pp. 551-558; Kohal, R.J., Att, W., Bachle, M., Butz, F., Ceramic abutments and ceramic oral implants. An update (2008) Periodontol 2000, 47, pp. 224-243; Degidi, M., Artese, L., Scarano, A., Perrotti, V., Gehrke, P., Piattelli, A., Inflammatory infiltrate, microvessel density, nitric oxide synthase expression, vascular endothelial growth factor expression, and proliferative activity in peri-implant soft tissues around titanium and zirconium oxide healing caps (2006) Journal of Periodontology, 77 (1), pp. 73-80. , DOI 10.1902/jop.2006.77.1.73; Kohal, R.J., Klaus, G., A zirconia implant-crown system: A case report (2004) International Journal of Periodontics and Restorative Dentistry, 24 (2), pp. 147-153; Sennerby, L., Dasmah, A., Larsson, B., Iverhed, M., Bone tissue responses to surface-modified zirconia implants: A histomorphometric and removal torque study in the rabbit (2005) Clin Implant Dent Relat Res, 71, pp. 13-20; Covacci, V., Bruzzese, N., Maccauro, G., Andreassi, C., Ricci, G.A., Piconi, C., Marmo, E., Cittadini, A., In vitro evaluation of the mutagenic and carcinogenic power of high purity zirconia ceramic (1999) Biomaterials, 20 (4), pp. 371-376. , DOI 10.1016/S0142-9612(98)00182-3, PII S0142961298001823; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23 (24), pp. 4897-4906. , DOI 10.1016/S0142-9612(02)00249-1, PII S0142961202002491; Garvie, R.C., Hannink, R.H., Pascoe, R.T., Ceramic steel? (1975) Nature, 258, pp. 703-704; Denry, I., Kelly, J.R., State of the art of zirconia for dental applications (2008) Dent Mater, 24, pp. 299-307; Ghosh, A., Suri, A.K., Pandey, M., Thomas, S., Rama Mohan, T.R., Rao, B.T., Nanocrystalline zirconia-yttria system-a Raman study (2006) Materials Letters, 60 (9-10), pp. 1170-1173. , DOI 10.1016/j.matlet.2005.10.102, PII S0167577X05010888; Li, M., Feng, Z., Xiong, G., Ying, P., Xin, Q., Li, C., Phase transformation in the surface region of zirconia detected by UV Raman spectroscopy (2001) J Phys Chem B, 105, pp. 8107-8111; Lughi, V., Clarke, D.R., Temperature dependence of the yttria-stabilized zirconia Raman spectrum (2007) J Appl Phys, 101; Argyriou, D.N., Howard, C.J., Re-investigation of yttria-tetragonal zirconia polycrystal (Y-TZP) by neutron powder diffraction - A cautionary tale (1995) J Appl Crystallogr, 28, pp. 206-208; Pascual, C., Duran, P., Subsolidus phase equilibria and ordering in the system ZrO 2-Y 2O 3 (1983) J Am Ceram Soc, 66, p. 23; Kelly, J.R., Denry, I., Stabilized zirconia as a structural ceramic: An overview (2008) Dent Mater, 24, pp. 289-298; Lughi, V., Sergo, V., Low temperature degradation aging of zirconia: A critical review of the relevant aspects in dentistry (2010) Dent Mater, 26, pp. 807-820; Chevalier, J., De Aza, A.H., Fantozzi, G., Schehl, M., Torrecillas, R., Extending the lifetime of ceramic orthopaedic implants (2000) Advanced Materials, 12 (21), pp. 1619-1621. , DOI 10.1002/1521-4095(200011)12:21<1619::AID-ADMA1619>3.0.CO;2-O; Kim, H.W., Kong, Y.M., Bae, C.J., Noh, Y.J., Kim, H.E., Sol-gel derived fluoro-hydroxyapatite biocoatings on zirconia substrate (2004) Biomaterials, 25, pp. 2919-2926; Lee, E.-J., Lee, S.-H., Kim, H.-W., Kong, Y.-M., Kim, H.-E., Fluoridated apatite coatings on titanium obtained by electron-beam deposition (2005) Biomaterials, 26 (18), pp. 3843-3851. , DOI 10.1016/j.biomaterials.2004.10.019, PII S0142961204009391; Vorobyev, A.Y., Guo, C., Femtosecond laser structuring of titanium implants (2007) Applied Surface Science, 253 (17), pp. 7272-7280. , DOI 10.1016/j.apsusc.2007.03.006, PII S0169433207004400; Perrie, W., Rushton, A., Gill, M., Fox, P., O'Neill, W., Femtosecond laser micro-structuring of alumina ceramic (2005) Applied Surface Science, 248 (1-4), pp. 213-217. , DOI 10.1016/j.apsusc.2005.03.005, PII S0169433205003806, 4th International Conference on Photo-Excited Processes and Applications 4-ICEPA; Teixeira, S., Monteiro, F.J., Ferraz, M.P., Vilar, R., Eugenio, S., Laser surface treatment of hydroxyapatite for enhanced tissue integration: Surface characterization and osteoblastic interaction studies (2007) Journal of Biomedical Materials Research - Part A, 81 (4), pp. 920-929. , DOI 10.1002/jbm.a.31073; Nayab, S.N., Jones, F.H., Olsen, I., Effects of calcium ion implantation on human bone cell interaction with titanium (2005) Biomaterials, 26 (23), pp. 4717-4727. , DOI 10.1016/j.biomaterials.2004.11.044, PII S0142961204010488; Kosmac, T., Oblak, C., Jevnikar, P., Funduk, N., Marion, L., The effect of surface grinding and sandblasting on flexural strength and reliability of Y-TZP zirconia ceramic (1999) Dental Materials, 15 (6), pp. 426-433. , PII S0109564199000706; Filiaggi, M.J., Pilliar, R.M., Abdulla, D., Evaluating sol-gel ceramic thin films for metal implant applications. II. Adhesion and fatigue properties of zirconia films on Ti-6Al-4V (1996) Journal of Biomedical Materials Research, 33 (4), pp. 239-256. , DOI 10.1002/(SICI)1097-4636(199624)33:4<239::AID-JBM4>3.0.CO;2-Q; Sollazzo, V., Pezzetti, F., Scarano, A., Piattelli, A., Bignozzi, C.A., Massari, L., Zirconium oxide coating improves implant osseointegration in vivo (2008) Dent Mater, 24, pp. 357-361; Sollazzo, V., Palmieri, A., Pezzetti, F., Bignozzi, C.A., Argazzi, R., Massari, L., Genetic effect of zirconium oxide coating on osteoblast-like cells (2008) J Biomed Mater Res B: Appl Biomater, 84, pp. 550-558; Kim, H.-W., Georgiou, G., Knowles, J.C., Koh, Y.-H., Kim, H.-E., Calcium phosphates and glass composite coatings on zirconia for enhanced biocompatibility (2004) Biomaterials, 25 (18), pp. 4203-4213. , DOI 10.1016/j.biomaterials.2003.10.094, PII S0142961203010470; Thian, E.S., Huang, J., Best, S.M., Barber, Z.H., Brooks, R.A., Rushton, N., Bonfield, W., The response of osteoblasts to nanocrystalline silicon-substituted hydroxyapatite thin films (2006) Biomaterials, 27 (13), pp. 2692-2698. , DOI 10.1016/j.biomaterials.2005.12.019, PII S0142961205011816; Klein, L., Sol-gel processing of silicates (1985) Annu Rev Mater Sci, 15, pp. 227-248; McDonagh, C., Sheridan, F., Butler, T., MacCraith, B.D., Characterisation of sol-gel-derived silica films (1996) Journal of Non-Crystalline Solids, 194 (1-2), pp. 72-77; Hench, L.L., Sol-gel materials for bioceramic applications (1997) Current Opinion in Solid State and Materials Science, 2 (5), pp. 604-610. , PII S1359028697800538; Garcia, C., Cere, S., Duran, A., Bioactive coatings prepared by sol-gel on stainless steel 316L (2004) J Non-Cryst Solids, 348, pp. 218-224; Garcia, C., Galliano, P., Cere, S., Electrochemical evaluation of resistance to localised corrosion of vitreous coatings containing particles applied on metallic substrates for biomedical applications (2003) Mater Lett, 57, pp. 1810-1814; Xia, Y., Whitesides, G.M., Soft lithography (1998) Angew Chem Int Ed, 37, pp. 550-575; Kim, E.J., Boehm, C.A., Mata, A., Fleischman, A.J., Muschler, G.F., Roy, S., Post microtextures accelerate cell proliferation and osteogenesis (2010) Acta Biomater, 6, pp. 160-169; Turner, A.M.P., Dowell, N., Turner, S.W.P., Kam, L., Isaacson, M., Turner, J.N., Craighead, H.G., Shain, W., Attachment of astroglial cells to microfabricated pillar arrays of different geometries (2000) Journal of Biomedical Materials Research, 51 (3), pp. 430-441. , DOI 10.1002/1097-4636(20000905)51:3<430::AID-JBM18>3.0.CO;2-C; Brunette, D.M., In vitro models of biological responses to implants (1999) Adv Dent Res, 13, p. 35; Chen, C.S., Mrksich, M., Huang, S., Whitesides, G.M., Ingber, D.E., Geometric control of cell life and death (1997) Science, 276 (5317), pp. 1425-1428. , DOI 10.1126/science.276.5317.1425; Flemming, R.G., Murphy, C.J., Abrams, G.A., Goodman, S.L., Nealey, P.F., Effects of synthetic micro- and nano-structured surfaces on cell behavior (1999) Biomaterials, 20 (6), pp. 573-588. , DOI 10.1016/S0142-9612(98)00209-9, PII S0142961298002099; Walboomers, X.F., Jansen, J.A., Cell and tissue behavior on micro-grooved surfaces (2001) Odontology, 89, pp. 2-11; Wilkinson, C.D.W., Riehle, M., Wood, M., Gallagher, J., Curtis, A.S.G., The use of materials patterned on a nano- and micro-metric scale in cellular engineering (2002) Materials Science and Engineering C, 19 (1-2), pp. 263-269. , DOI 10.1016/S0928-4931(01)00396-4, PII S0928493101003964, Current trends in Nanotechnologies: From Materials to Systems; Bettinger, C.J., Langer, R., Borenstein, J.T., Engineering substrate topography at the micro- and nanoscale to control cell function (2009) Angew Chem Int Ed, 48, pp. 5406-5415; Pelaez-Vargas, A., Ferrell, N., Fernandes, M.H., Hansford, D., Monteiro, F.J., Cells spreading on micro-fabricated silica thin film coatings (2009) Microsc Microanal, 15, pp. 77-78; Pelaez-Vargas, A., Ferrell, N., Fernandes, M.H., Hansford, D.J., Monteiro, F.J., Cellular alignment induction during early in vitro culture stages using micropatterned glass coatings produced by sol-gel process (2009) Key Eng Mater, 396-398, p. 303; Singhvi, R., Stephanopoulos, G., Wang, D.I., Effects of substratum morphology on cell physiology (1994) Biotechnol Bioeng, 43, pp. 764-771; Von Recum, A.F., Van Kooten, T.G., The influence of micro-topography on cellular response and the implications for silicone implants (1995) J Biomater Sci Polym Ed, 7, pp. 181-198; Pelaez-Vargas, A., Gallego-Perez, D., Ferrell, N., Fernandes, M.H., Hansford, D., Monteiro, F.J., Early spreading and propagation of human bone marrow stem cells on isotropic and anisotropic topographies of silica thin films produced via microstamping (2010) Microsc Microanal, 16, pp. 670-676; Brett, P.M., Harle, J., Salih, V., Mihoc, R., Olsen, I., Jones, F.H., Tonetti, M., Roughness response genes in osteoblasts (2004) Bone, 35 (1), pp. 124-133. , DOI 10.1016/j.bone.2004.03.009, PII S8756328204001140; Klinge, B., Hultin, M., Berglundh, T., Peri-implantitis (2005) Dental Clinics of North America, 49 (3 SPEC. ISS.), pp. 661-676. , DOI 10.1016/j.cden.2005.03.007, PII S0011853205000236; Leonhardt, A., Renvert, S., Dahlen, G., Microbial findings at failing implants (1999) Clin Oral Implants Res, 10, pp. 339-345; Zinelis, S., Thomas, A., Syres, K., Silikas, N., Eliades, G., Surface characterization of zirconia dental implants (2010) Dent Mater, 26, pp. 295-305; Marzolin, C., Smith, S.P., Prentiss, M., Whitesides, G.M., Fabrication of glass microstructures by micro-molding of sol-gel precursors (1998) Advanced Materials, 10 (8), pp. 571-574; Santucci, S., Di Nardo, S., Lozzi, L., Passacantando, M., Picozzi, P., XPS analysis on SiO 2 sol-gel thin films (1995) J Electron Spectrosc Relat Phenom, 76, pp. 623-628; Braet, F., De Zanger, R., Wisse, E., Drying cells for SEM, AFM and TEM by hexamethyldisilazane: A study on hepatic endothelial cells (1997) Journal of Microscopy, 186 (1), pp. 84-87
Keywords: Adhesion; article; Biological behavior; biomaterial; biomedical and dental materials; cell adhesion; Cell culture; Cell Line; cell proliferation; Cell response; cell survival; Ceramic implants; ceramics; chemistry; Coated Materials, Biocompatible; Coatings; confocal microscopy; crystallography; Dental implant materials; Dental implantology; Dental Implants; Dental Materials; Dental prostheses; diagnostic agent; dyes, reagents, indicators, markers and buffers; Gels; Gold standards; Growth kinetics; Guided tissue regeneration; Guided Tissue Regeneration, Periodontal; heat; Hot Temperature; human; Human osteoblast-like cells; Humans; In-vitro; Indicators and Reagents; Lithography; materials testing; Micropatterned; Microscopy, Confocal; Microscopy, Electron, Scanning; osteoblast; Osteoblast-like cells; Osteoblastic cell adhesion; Osteoblasts; oxazine derivative; Oxazines; Peri-implantitis; Periodontal tissue; periodontics; phase transition; physiology; Raman spectrometry; resazurin; Scanning electron microscopy; Silica; Silica coatings; Silica film; Silica surface; silicon dioxide; Soft lithography; Sol-gel; Sol-gel chemistry; Sol-gel process; Sol-gel technology; Sol-gels; Sols; Spectrum Analysis, Raman; Stabilized zirconia; Statistical analysis; Surface modification techniques; Surface morphology; Surface Properties; surface property; Surface-modified; Surfaces; time; Time Factors; Tissue; Tissue growth; Titanium; Titanium implants; tooth implantation; Top surface; X ray diffraction; X-Ray Diffraction; xanthene derivative; Xanthenes; yttria stabilized tetragonal zirconia; Yttria stabilized zirconia; yttrium; Yttrium alloys; Zirconia; Zirconia materials; zirconium

Knowledge of adverse neonatal outcome alters clinicians' interpretation of the intrapartum cardiotocograph - Ayres-de-Campos, D.; Arteiro, D.; Costa-Santos, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2011)
Objective: To evaluate the impact of knowledge of neonatal outcome on clinicians' interpretation of the intrapartum cardiotocograph (CTG). Design: Prospective evaluation of pre-recorded cases. Setting: Five maternity hospitals. Population: From a database of intrapartum CTGs acquired with a scalp electrode in singleton near-term fetuses, 20 tracings were sequentially selected from cases with newborn umbilical artery pH < 7.05 and 20 from cases with pH > 7.20. Methods: Five experienced obstetricians practising in different maternity hospitals were asked to analyse the 40 tracings individually, according to the International Federation of Gynaecology and Obstetrics guidelines. In a first round, clinicians were given no information on neonatal outcome. In a second round, carried out 2 months later, clinicians were asked to analyse the same tracings, but the order was randomly altered and information on the newborn's arterial pH was provided. Clinicians were not informed of the purpose of the study or whether the tracings were the same. Main outcome measures: The incidence of individual fetal heart rate feature identification and tracing classification, before and after neonatal outcome was made available. Results: In the group with pH < 7.05, repetitive decelerations and reduced variability were more common in the second round (P < 0.001 and P = 0.001, respectively), as was a pathological classification (P = 0.002); variable decelerations were less common (P = 0.008). In the group with normal pH, less tracings in the second round had prolonged decelerations (P = 0.013) and no accelerations (P = 0.013), but more had pronounced decelerations (P = 0.031) and reduced variability (P = 0.007); there was a reduction in pathological classifications, but this difference failed to reach statistical significance (P = 0.051). Conclusions: A knowledge of adverse neonatal outcome leads to a more severe classification of the intrapartum CTG, which derives mainly from the evaluation of decelerations and variability. © 2011 The Authors BJOG An International Journal of Obstetrics and Gynaecology © 2011 RCOG.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2011.03003.xPubMed ID: 21609381Language of Original Document: EnglishCorrespondence Address: Ayres-de-Campos, D.; Departmento de Ginecologia e Obstetrícia, Faculdade de Medicina do Porto, 4200-309 Porto, Portugal; email: dcampos@med.up.ptReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales and Northern Ireland, , CEMACH - Centre for Maternal and Child Enquiries (previously Confidential Enquiries into Maternal and Child Health). London: CEMACH;(1997) CESDI - Confidential Enquiry into Stillbirths and Deaths in Infancy, , 4th Annual Report. London: CESDI; Wood, C., Renou, P., Oats, J., A controlled trial of fetal heart rate monitoring in a low-risk obstetric population (1981) American Journal of Obstetrics and Gynecology, 141 (5), pp. 527-534; MacDonald, D., Grant, A., Sheridan-Pereira, M., The Dublin randomized controlled trial of intrapartum fetal heart rate monitoring (1985) American Journal of Obstetrics and Gynecology, 152 (5), pp. 524-539; Shy, K.K., Luthy, D.A., Bennett, F.C., Whitfield, M., Larson, E.B., Van Belle, G., Hughes, J.P., Stenchever, M.A., Effects of electronic fetal-heart-rate monitoring, as compared with periodic auscultation, on the neurologic development of premature infants (1990) New England Journal of Medicine, 322 (9), pp. 588-593; Dillner, L., Babies' deaths linked to suboptimal care (1995) Br Med J, 310, p. 757; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Palomaki, O., Luukkaala, T., Luoto, R., Tuimala, R., Intrapartum cardiotocography - The dilemma of interpretational variation (2006) Journal of Perinatal Medicine, 34 (4), pp. 298-302. , DOI 10.1515/JPM.2006.057, PII JPME344298; Westerhuis, M., Van Horen, E., Kwee, A., Van Der Tweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-551; Caplan, R.A., Posner, K.L., Cheney, F.W., Effect of outcome on physician judgment of appropriateness of care (1991) J Am Med Assoc, 265, pp. 1957-1960; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167. , FIGO News; Amer-Wahlin, I., Hellsten, C., Noren, H., Hagberg, H., Herbst, A., Kjellmer, I., Lilja, H., Marsal, K., Cardiotocography only versus cardiotocography plus ST analysis of fetal electrocardiogram for intrapartum fetal monitoring: A Swedish randomised controlled trial (2001) Lancet, 358 (9281), pp. 534-538. , DOI 10.1016/S0140-6736(01)05703-8; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) British Journal of Obstetrics and Gynaecology, 101 (12), pp. 1054-1063; Figueras, F., Albela, S., Bonino, S., Palacio, M., Barrau, E., Hernandez, S., Casellas, C., Cararach, V., Visual analysis of antepartum fetal heart rate tracings: Inter- and intra-observer agreement and impact of knowledge of neonatal outcome (2005) Journal of Perinatal Medicine, 33 (3), pp. 241-245. , http://www.extenza-eps.com/extenza/loadPDF?objectIDValue=64432, DOI 10.1515/JPM.2005.044; Zain, H.A., Wright, J.W., Parrish, G.E., Diehl, S.J., Interpreting the fetal heart rate tracing: Effect of knowledge of neonatal outcome (1998) Journal of Reproductive Medicine for the Obstetrician and Gynecologist, 43 (4), pp. 367-370; Almström, H., Axelsson, O., Ekman, G., Ingemarsson, I., Maesel, A., Arström, K., Umbilical artery velocimetry may influence clinical interpretation of intrapartum cardiotocograms (1995) Acta Obstet Gynecol Scand, 74, pp. 526-529; Spencer, J.A.D., Clinical overview of cardiotocography (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 4-7; Ayres-de-Campos, D., Bernardes, J., Early, variable and late decelerations: Can a consensus be reached in their identification? (1999) Int J Gynecol Obstet, 65, pp. 305-306; Capstick, J.B., Edwards, P.J., Trends in obstetric malpractice claims (1990) Lancet, 336 (8720), pp. 931-932. , DOI 10.1016/0140-6736(90)92291-O; Symonds, E.M., Litigation and the cardiotocogram (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 8-9; Williams, B., Arulkumaran, S., Cardiotocography and medicolegal issues (2004) Best Practice and Research: Clinical Obstetrics and Gynaecology, 18 (3), pp. 457-466. , DOI 10.1016/j.bpobgyn.2004.02.005, PII S1521693404000318
Keywords: adverse outcome; Agreement; article; bradycardia; Cardiotocography; clinical competence; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus heart rate; fetus outcome; health practitioner; Heart rate; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; incidence; Infant, Newborn; intrapartum care; Labor, Obstetric; medical practice; pH; practice guideline; Practice Guidelines as Topic; Pregnancy; Pregnancy Outcome; priority journal; Prospective Studies; Questionnaires; Reference Standards; Reproducibility of Results; Research Design; Risk Factors; Sweden; tachycardia; umbilical artery

Layer-by-layer self-assembly of chitosan and poly(γ-glutamic acid) into polyelectrolyte complexes - Antunes, J.C.; Pereira, C.L.; Molinos, M.; Ferreira-da-Silva, F.; Dessi, M.; Gloria, A.; Ambrosio, L.; Gonca̧lves, R.M.; Barbosa, M.A. (BiomacromoleculesBiomacromolecules, 2011)
Chitosan (Ch) is a nontoxic and biocompatible polysaccharide extensively used in biomedical applications. Ch, as a polycation, can be combined with anionic polymers by layer-bylayer (LbL) self-assembly, giving rise to multilayered complexed architectures. These structures can be used in tissue engineering strategies, as drug delivery systems, or artificial matrices mimicking the extracellular microenvironment. In this work, Ch was combined with poly(γ-glutamic acid) (γ-PGA). γ-PGA is a polyanion, which was microbially produced, and is known for its low immunogenic reaction and low cytotoxicity. Multilayered ultrathin films were assembled by LbL, with a maximum of six layers. The interaction between both polymers was analyzed by: ellipsometry, quartz crystal microbalance with dissipation, Fourier transform infrared spectroscopy, atomic force microscopy, and zeta potential measurements. Ch/γ-PGA polyelectrolyte multilayers (PEMs) revealed no cytotoxicity according to ISO 10993-5. Overall, this study demonstrates that Ch can interact electrostatically with γ-PGA forming multilayered films. Furthermore, this study provides a comprehensive characterization of Ch/γ-PGA PEM structures, elucidating the contribution of each layer for the nanostructured films. These model surfaces can be useful substrates to study cell-biomaterial interactions in tissue regeneration. © 2011 American Chemical Society.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm2008235PubMed ID: 22032302Language of Original Document: EnglishCorrespondence Address: Antunes, J.C.; INEB - Instituto de Engenharia Biomédica, Porto, Portugal; email: joana.antunes@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; glutamic acid, 11070-68-1, 138-15-8, 56-86-0, 6899-05-4; Biocompatible Materials; Chitosan, 9012-76-4; Electrolytes; Polyglutamic Acid, 25513-46-6; Viscoelastic Substances; poly(gamma-glutamic acid)References: Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., Ultrathin polymer coatings by complexation of polyelectrolytes at interfaces: Suitable materials, structure and properties (2000) Macromol. Rapid Commun., 21, pp. 319-348;Schonhoff, M., Layered polyelectrolyte complexes: Physics of formation and molecular properties (2003) J. Phys.: Condens. Matter, 15, pp. R1781-R1808; Von Klitzing, R., Internal structure of polyelectrolyte multilayer assemblies (2006) Phys. Chem. Chem. Phys., 8, pp. 5012-5033; Iler, R.K., Multilayers of colloidal particles (1966) J. Colloid Interface Sci., 21, pp. 569-594; Zhang, X., Chen, H., Zhang, H., Layer-by-layer assembly: From conventional to unconventional methods (2007) Chemical Communications, (14), pp. 1395-1405. , DOI 10.1039/b615590a; Decher, G., Hong, J.D., Schmitt, J., Buildup of ultrathin multilayer films by a self-assembly process. 3. Consecutively alternating adsorption of anionic and cationic polyelectrolytes on charged surfaces (1992) Thin Solid Films, 210, pp. 831-835; Boudou, T., Crouzier, T., Ren, K.F., Blin, G., Picart, C., Multiple functionalities of polyelectrolyte multilayer films: New biomedical applications (2010) Adv. Mater., 22, pp. 441-467; Schlenoff, J.B., Retrospective on the future of polyelectrolyte multilayers (2009) Langmuir, 25, pp. 14007-14010; Ariga, K., Hill, J.P., Ji, Q.M., Layer-by-layer assembly as a versatile bottom-up nanofabrication technique for exploratory research and realistic application (2007) Phys. Chem. Chem. Phys., 9, pp. 2319-2340; Meng, S., Liu, Z., Shen, L., Guo, Z., Chou, L.L., Zhong, W., Du, Q., Ge, J., The effect of a layer-by-layer chitosan-heparin coating on the endothelialization and coagulation properties of a coronary stent system (2009) Biomaterials, 30, pp. 2276-2283; De Geest, B.G., Jonas, A.M., Demeester, J., De Smedt, S.C., Glucose-responsive polyelectrolyte capsules (2006) Langmuir, 22 (11), pp. 5070-5074. , DOI 10.1021/la053368o; Dimitrova, M., Affolter, C., Meyer, F., Nguyen, I., Richard, D.G., Schuster, C., Bartenschlager, R., Baumert, T.F., Sustained delivery of siRNAs targeting viral infection by celldegradable multilayered polyelectrolyte films (2008) Proc. Natl. Acad. Sci. U.S.A., 105, pp. 16320-16325; Crouzier, T., Ren, K., Nicolas, C., Roy, C., Picart, C., Layer-bylayer films as a biomimetic reservoir for rhBMP-2 delivery: Controlled differentiation of myoblasts to osteoblasts (2009) Small, 5, pp. 598-608; He, L., Dexter, A.F., Middelberg, A.P.J., Biomolecular engineering at interfaces (2006) Chemical Engineering Science, 61 (3), pp. 989-1003. , DOI 10.1016/j.ces.2005.05.064, PII S000925090500518X, Biomolecular Engineering; Chua, P.H., Neoh, K.G., Shi, Z., Kang, E.T., Structural stability and bioapplicability assessment of hyaluronic acid-chitosan polyelectrolyte multilayers on titanium substrates (2008) J. Biomed. Mater. Res., Part A, 87 A, pp. 1061-1074; Decher, G., Fuzzy nanoassemblies: Toward layered polymeric multicomposites (1997) Science, 277 (5330), pp. 1232-1237. , DOI 10.1126/science.277.5330.1232; Ozin, G.A., Hou, K., Lotsch, B.V., Cademartiri, L., Puzzo, D.P., Scotognella, F., Ghadimi, A., Thomson, J., Nanofabrication by selfassembly (2009) Mater. Today, 12, pp. 12-23; Dubas, S.T., Schlenoff, J.B., Factors controlling the growth of polyelectrolyte multilayers (1999) Macromolecules, 32 (24), pp. 8153-8160. , DOI 10.1021/ma981927a; Kumar, M.N.V.R., Muzzarelli, R.A.A., Muzzarelli, C., Sashiwa, H., Domb, A.J., Chitosan chemistry and pharmaceutical perspectives (2004) Chemical Reviews, 104 (12), pp. 6017-6084. , DOI 10.1021/cr030441b; Yi, H., Wu, L.-Q., Bentley, W.E., Ghodssi, R., Rubloff, G.W., Culver, J.N., Payne, G.F., Biofabrication with chitosan (2005) Biomacromolecules, 6 (6), pp. 2881-2894. , DOI 10.1021/bm050410l; Berger, J., Reist, M., Mayer, J.M., Felt, O., Gurny, R., Structure and interactions in chitosan hydrogels formed by complexation or aggregation for biomedical applications (2004) European Journal of Pharmaceutics and Biopharmaceutics, 57 (1), pp. 35-52. , DOI 10.1016/S0939-6411(03)00160-7; Rinaudo, M., Chitin and chitosan: Properties and applications (2006) Progress in Polymer Science (Oxford), 31 (7), pp. 603-632. , DOI 10.1016/j.progpolymsci.2006.06.001, PII S0079670006000530; Sogias, I.A., Khutoryanskiy, V.V., Williams, A.C., Exploring the factors affecting the solubility of chitosan in water (2010) Macromol. Chem. Phys., 211, pp. 426-433; Sorlier, P., Denuziere, A., Viton, C., Domard, A., Relation between the degree of acetylation and the electrostatic properties of chitin and chitosan (2001) Biomacromolecules, 2 (3), pp. 765-772. , DOI 10.1021/bm015531+; Krayukhina, M.A., Samoilova, N.A., Yamskov, I.A., Polyelectrolyte complexes of chitosan: Formation, properties, and applications (2008) Usp. Khim., 77, pp. 854-869; Buescher, J.M., Margaritis, A., Microbial biosynthesis of polyglutamic acid biopolymer and applications in the biopharmaceutical, biomedical and food industries (2007) Critical Reviews in Biotechnology, 27 (1), pp. 1-19. , DOI 10.1080/07388550601166458, PII 773236840; Shih, I.L., Van, Y.T., Shen, M.H., Biomedical applications of chemically and microbiologically synthesized poly(glutamic acid) and poly(lysine) (2004) Mini-Rev. Med. Chem., 4, pp. 179-188; Nelson, D.L., Cox, M.M., Amino acids peptides and proteins (2005) Lehninger Principles of Biochemistry, pp. 78-79. , 4th ed.; W. H. Freeman and Company: New York; Edde, B., Rossier, J., Lecaer, J.P., Desbruyeres, E., Gros, F., Denoulet, P., Posttranslational glutamylation of alpha-tubulin (1990) Science, 247, pp. 83-85; Candela, T., Fouet, A., Poly-γ-glutamate in bacteria (2006) Mol. Microbiol., 60, pp. 1091-1098; Rhie, G.-E., Roehrl, M.H., Mourez, M., Collier, R.J., Mekalanos, J.J., Wang, J.Y., A dually active anthrax vaccine that confers protection against both bacilli and toxins (2003) Proceedings of the National Academy of Sciences of the United States of America, 100 (19), pp. 10925-10930. , DOI 10.1073/pnas.1834478100; Schneerson, R., Kubler-Kielb, J., Liu, T.-Y., Dai, Z.-D., Leppla, S.H., Yergey, A., Backlund, P., Robbins, J.B., Poly(γ-D-glutamic acid) protein conjugates induce IgG antibodies in mice to the capsule of Bacillus anthracis: A potential addition to the anthrax vaccine (2003) Proceedings of the National Academy of Sciences of the United States of America, 100 (15), pp. 8945-8950. , DOI 10.1073/pnas.1633512100; Prescott, A.G., Stock II, L.R., (2005) Method for Producing Medical and Commercial Grade Poly-γ-glutamic Acid of High Molecular Weight, , U. S. Patent 20050095679; Prodhomme, E.J.F., Tutt, A.L., Glennie, M.J., Bugg, T.D.H., Multivalent Conjugates of Poly-γ-D-glutamic Acid from Bacillus licheniformis with Antibody F(abβ) and Glycopeptide Ligands (2003) Bioconjugate Chemistry, 14 (6), pp. 1148-1155. , DOI 10.1021/bc020019m; Sutherland, M.D., Thorkildson, P., Parks, S.D., Kozel, T.R., In vivo fate and distribution of poly-γ-D-glutamic acid, the capsular antigen from Bacillus anthracis (2008) Infection and Immunity, 76 (3), pp. 899-906. , DOI 10.1128/IAI.01176-07; Serizawa, T., Goto, H., Kishida, A., Endo, T., Akashi, M., Improved alternate deposition of biodegradable naturally occurring polymers onto a quartz crystal microbalance (1999) J. Polym. Sci., Part A: Polym. Chem., 37, pp. 801-804; Tachaboonyakiat, W., Serizawa, T., Endo, T., Akashi, M., The influence of molecular weight over the ultrathin films of biodegradable polyion complexes between chitosan and poly(γ-glutamic acid) (2000) Polym. J., 32, pp. 481-485; Hsieh, C.Y., Tsai, S.P., Wang, D.M., Chang, Y.N., Hsieh, H.J., Preparation of γ-PGA/chitosan composite tissue engineering matrices (2005) Biomaterials, 26, pp. 5617-5623; Kang, H.S., Park, S.H., Lee, Y.G., Son, T.I., Polyelectrolyte complex hydrogel composed of chitosan and poly(γ-glutamic acid) for biological application: Preparation, physical properties, and cytocompatibility (2007) J. Appl. Polym. Sci., 103, pp. 386-394; Tsao, C.T., Chang, C.H., Lin, Y.Y., Wu, M.F., Wang, J.L., Han, J.L., Hsieh, K.H., Antibacterial activity and biocompatibility of a chitosan-γ- poly(glutamic acid) polyelectrolyte complex hydrogel (2010) Carbohydr. Res., 345, pp. 1774-1780; Hajdu, I., Bodnar, M., Filipcsei, G., Hartmann, J.F., Daroczi, L., Zrinyi, M., Borbely, J., Nanoparticles prepared by self-assembly of chitosan and poly-γ-glutamic acid (2008) Colloid Polym. Sci., 286, pp. 343-350; Lin, Y.H., Chung, C.K., Chen, C.T., Liang, H.F., Chen, S.C., Sung, H.W., Preparation of nanoparticles composed of chitosan/poly-γ-glutamic acid and evaluation of their permeability through Caco-2 cells (2005) Biomacromolecules, 6, pp. 1104-1112; Imoto, T., Kida, T., Matsusaki, M., Akashi, M., Preparation and unique pH-responsive properties of novel biodegradable nanocapsules composed of poly(γ-glutamic acid) and chitosan as weak polyelectrolytes (2010) Macromol. Biosci., 10, pp. 271-277; Crompton, K.E., Goud, J.D., Bellamkonda, R.V., Gengenbach, T.R., Finkelstein, D.I., Horne, M.K., Forsythe, J.S., Polylysine-functionalised thermoresponsive chitosan hydrogel for neural tissue engineering (2007) Biomaterials, 28 (3), pp. 441-449. , DOI 10.1016/j.biomaterials.2006.08.044, PII S0142961206007642; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydrate Polymers, 29 (1), pp. 63-68. , DOI 10.1016/0144-8617(95)00147-6; Kunioka, M., Goto, A., Biosynthesis of poly(γ-glutamic acid) from L-glutamic acid, citric acid, and ammonium sulfate in Bacillus subtilis IFO3335 (1994) Applied Microbiology and Biotechnology, 40 (6), pp. 867-872. , DOI 10.1007/s002530050082; Kubota, H., Matsunobu, T., Uotani, K., Takebe, H., Satoh, A., Tanaka, T., Taniguchi, M., Production of poly(γ-glutamic acid) by Bacillus subtilis F-2-01 (1993) Biosci., Biotechnol., Biochem., 57, pp. 1212-1213; Ashiuchi, M., Soda, K., Misono, H., A poly-γ-glutamate synthetic system of Bacillus subtilis IFO 3336: Gene cloning and biochemical analysis of poly-γ-glutamate produced by Escherichia coli clone cells (1999) Biochemical and Biophysical Research Communications, 263 (1), pp. 6-12. , DOI 10.1006/bbrc.1999.1298; Yamaguchi, F., Ogawa, Y., Kikuchi, M., Yuasa, K., Motai, H., Detection of γ-polyglutamic acid (γ-PGA) by SDS-PAGE (1996) Biosci., Biotechnol., Biochem., 60, pp. 255-258; Scolnik, Y., Portnaya, I., Cogan, U., Tal, S., Haimovitz, R., Fridkin, M., Elitzur, A.C., Shinitzky, M., Subtle differences in structural transitions between poly-L-and poly-D-amino acids of equal length in water (2006) Phys. Chem. Chem. Phys., 8, pp. 333-339; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) Journal of Biomedical Materials Research - Part A, 67 (1), pp. 158-171; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Da Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Transactions on Magnetics, 35 (5 PART 3), pp. 4361-4367. , DOI 10.1109/20.799086; Ambrosio, L., Borzacchiello, A., Netti, P.A., Nicolais, L., Properties of new materials: Rheological study on hyaluronic acid and its derivative solutions (1999) Journal of Macromolecular Science - Pure and Applied Chemistry, 36 A (7-8), pp. 991-1000; Horcas, I., Fernandez, R., Gomez-Rodriguez, J.M., Colchero, J., Gomez-Herrero, J., Baro, A.M., WSXM: A software for scanning probe microscopy and a tool for nanotechnology (2007) Rev. Sci. Instrum., 78, p. 1; Martins, M.C.L., Ochoa-Mendes, V., Ferreira, G., Barbosa, J.N., Curtin, S.A., Ratner, B.D., Barbosa, M.A., Interactions of leukocytes and platelets with poly(lysine/leucine) immobilized on tetraethylene glycol-terminated self-assembled monolayers (2011) Acta Biomater., 7, pp. 1949-1955; Werner, C., Konig, U., Augsburg, A., Arnhold, C., Korber, H., Zimmermann, R., Jacobasch, H.-J., Electrokinetic surface characterization of biomedical polymers - A survey (1999) Colloids and Surfaces A: Physicochemical and Engineering Aspects, 159 (2-3), pp. 519-529. , DOI 10.1016/S0927-7757(99)00290-3, PII S0927775799002903; Fairbrother, F., Mastin, H., Studies in electro-endosmosis part I (1924) J. Chem. Soc., 125, pp. 2319-2330; Voinova, M.V., Rodahl, M., Jonson, M., Kasemo, B., Viscoelastic acoustic response of layered polymer films at fluid-solid interfaces: Continuum mechanics approach (1999) Phy. Scr., 59, pp. 391-396; Hook, F., Kasemo, B., Variations in coupled water, viscoelastic properties, and film thickness of a Mefp-1 protein film during adsorption and cross-linking: A quartz crystal microbalance with dissipation monitoring, ellipsometry, and surface plasmon resonance study (2001) Analytical Chemistry, 73 (24), pp. 5796-5804. , DOI 10.1021/ac0106501; Hook, F., Rodahl, M., Brzezinski, P., Kasemo, B., Measurements using the quartz crystal microbalance technique of ferritin monolayers on methyl-thiolated gold: Dependence of energy dissipation and saturation coverage on salt concentration (1998) Journal of Colloid and Interface Science, 208 (1), pp. 63-67. , DOI 10.1006/jcis.1998.5774; Larsson, C., Rodahl, M., Hook, F., Characterization of DNA immobilization and subsequent hybridization on a 2D arrangement of streptavidin on a biotin-modified lipid bilayer supported on SiO 2 (2003) Analytical Chemistry, 75 (19), pp. 5080-5087. , DOI 10.1021/ac034269n; Sauerbrey, G., Verwendung von schwingquarzen zur wagung dunner schichten und zur mikrowagung (1959) Z. Phys., 155, pp. 206-222; Schlenoff, J.B., Dubas, S.T., Mechanism of polyelectrolyte multilayer growth: Charge overcompensation and distribution (2001) Macromolecules, 34 (3), pp. 592-598. , DOI 10.1021/ma0003093; Kim, D.K., Han, S.W., Kim, C.H., Hong, J.D., Kim, K., Morphology of multilayers assembled by electrostatic attraction of oppositely charged model polyelectrolytes (1999) Thin Solid Films, 350, pp. 153-160; Picart, C., Lavalle, Ph., Hubert, P., Cuisinier, F.J.G., Decher, G., Schaaf, P., Voegel, J.-C., Buildup mechanism for poly(L-lysine)/hyaluronic acid films onto a solid surface (2001) Langmuir, 17 (23), pp. 7414-7424. , DOI 10.1021/la010848g; Richert, L., Lavalle, P., Payan, E., Shu, X.Z., Prestwich, G.D., Stoltz, J.F., Schaaf, P., Picart, C., Layer by layer buildup of polysaccharide films: Physical chemistry and cellular adhesion aspects (2004) Langmuir, 20, pp. 448-458; Tsao, C.T., Hang, C.H., Lin, Y.Y., Wu, M.F., Wang, J.L., Young, T.H., Han, J.L., Hsieh, K.H., Evaluation of chitosan/γ-poly(glutamic acid) polyelectrolyte complex for wound dressing materials (2011) Carbohydr. Polym., 84, pp. 812-819; Bonazzola, C., Calvo, E.J., A Fourier transform infrared reflection-absorption spectroscopy study of redox polyelectrolyte films (2003) Langmuir, 19, pp. 5279-5286; Boulmedais, F., Ball, V., Schwinte, P., Frisch, B., Schaaf, P., Voegel, J.C., Buildup of exponentially growing multilayer polypeptide films with internal secondary structure (2003) Langmuir, 19, pp. 440-445; Boulmedais, F., Bozonnet, M., Schwinte, P., Voegel, J.C., Schaaf, P., Multilayered polypeptide films: Secondary structures and effect of various stresses (2003) Langmuir, 19, pp. 9873-9882; He, L.M., Neu, M.P., Vanderberg, L.A., Bacillus lichenformis γ-glutamyl exopolymer: Physicochemical characterization and U(VI) interaction (2000) Environmental Science and Technology, 34 (9), pp. 1694-1701. , DOI 10.1021/es991119e; Chan, Y.H.M., Schweiss, R., Werner, C., Grunze, M., Electrokinetic characterization of oligo-and poly(ethylene glycol)-terminated self-assembled monolayers on gold and glass surfaces (2003) Langmuir, 19, pp. 7380-7385; Giesbers, M., Kleijn, J.M., Cohen Stuart, M.A., The electrical double layer on gold probed by electrokinetic and surface force measurements (2002) Journal of Colloid and Interface Science, 248 (1), pp. 88-95. , DOI 10.1006/jcis.2001.8144; Schlenoff, J.B., Ly, H., Li, M., Charge and mass balance in polyelectrolyte multilayers (1998) Journal of the American Chemical Society, 120 (30), pp. 7626-7634. , DOI 10.1021/ja980350+; Rodahl, M., Hook, F., Fredriksson, C., Keller, C.A., Krozer, A., Brzezinski, P., Voinova, M., Kasemo, B., Simultaneous frequency and dissipation factor QCM measurements of biomolecular adsorption and cell adhesion (1997) Faraday Discussions, 107, pp. 229-246; Guzman, E., San Miguel, V., Peinado, C., Ortega, F., Rubio, R.C., Polyelectrolyte multilayers containing triblock copolymers of different charge ratio (2010) Langmuir, 26, pp. 11494-11502; Salomaki, M., Laiho, T., Kankare, J., Counteranion-controlled properties of polyelectrolyte multilayers (2004) Macromolecules, 37 (25), pp. 9585-9590. , DOI 10.1021/ma048701u; Dutta, A.K., Nayak, A., Belfort, G., Viscoelastic properties of adsorbed and cross-linked polypeptide and protein layers at a solidliquid interface (2008) J. Colloid Interface Sci., 324, pp. 55-60
Keywords: Amino acids; Anionic polymers; article; Atomic force microscopy; Atomic spectroscopy; Biocompatible Materials; Biocompatible polysaccharides; Biomaterials; Biomedical applications; Cell-biomaterial interactions; chemical interaction; chitosan; controlled study; Cytotoxicity; Drug delivery; drug delivery system; Drug Delivery Systems; Electrolytes; ellipsometry; enzyme activity; Extracellular; Fourier transform infrared spectroscopy; Glutamic acid; immunogenicity; infrared spectroscopy; Layer by layer self assembly; Medical applications; microenvironment; Microenvironments; Microscopy, Atomic Force; Model surface; Models, Molecular; Multi-layered; Multi-layered films; Multilayers; nanofilm; Nanostructured Films; polyanion; Polyanions; Polycations; polyelectrolyte; Polyelectrolyte complexes; Polyelectrolyte multilayer; Polyelectrolytes; Polyethylenes; polyglutamic acid; Polymers; priority journal; Programmed control systems; Quartz; quartz crystal microbalance; Quartz crystal microbalance with dissipation; Self assembly; Tissue; Tissue engineering; Tissue regeneration; Ultrathin films; Viscoelastic Substances; Zeta potential; Zeta potential measurements

The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement - Costa-Santos, C.; Bernardes, J.; Ayres-de-Campos, D.; Costa, A.; Costa, C. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Objective: To compare the interpretation of agreement in the prediction of neonatal outcome variables, using the limits of agreement (LA) and the intraclass correlation coefficient (ICC). Study Design and Setting: Three obstetricians were asked to predict neonatal outcomes independently based on the evaluation of intrapartum cardiotocographic tracings. Interobserver agreement was assessed with the LA and the ICC, and the results obtained were interpreted by six clinicians and six statisticians on a scale that established agreement as very poor, poor, fair, good, or very good. Results: Interpretation of the LA results was less consensual than the ICC results, with proportions of agreement of 0.36 (95% confidence interval [CI]: 0.28-0.44) vs. 0.63 (95% CI: 0.54-0.73), respectively. LA results suggested a fair to good agreement among obstetricians, whereas interpretation of ICC results suggested a poor to fair agreement. LA results were more plausible with reality, suggesting that obstetricians predicted neonatal outcomes better than randomly generated values, whereas it was not always the case with the ICC. Conclusions: LA and ICC can provide inconsistent results in agreement studies. Accordingly, in the absence of better strategies to assess agreement, both should be used for this purpose, but their results need to be interpreted with caution keeping their respective limitations in mind. © 2011 Elsevier Inc. All rights reserved.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JCEPEdoi: 10.1016/j.jclinepi.2009.11.010PubMed ID: 20189765Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: De Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127;Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Santos, C.C., Pereira, C.A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2003) J Clin Epidemiol, 56, pp. 963-967; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Bartko, J.J., The intraclass correlation coefficient as a measure of reliability (1966) Psychol Rep, 19, pp. 3-11; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Burdock, E., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Person Psychol, 16, pp. 373-384; Casey, B.M., McLntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of newborn infants (2001) N Engl J Med, 344, pp. 467-471; Van De Riet, J.E., Vandenbussche, F.P., Le Cessie, S., Keirse, M.J., Newborn assessment and long-term adverse outcome: A systematic review (1999) Am J Obstet Gynecol, 180, pp. 1024-1029; Shrout, P.E., Fleiss, J.L., Intraclass correlations: Uses in assessing rater reliability (1979) Psychol Bull, 86, pp. 420-427; Fleiss, J.U., Davies, M., Measuring nominal scale agreement among many raters (1971) Psychol Bull, 76, pp. 378-382; Carpenter, J., Bithell, J., Bootstrap confidence intervals: When, which, what? A practical guide for medical statisticians (2000) Stat Med, 19, pp. 1141-1164; Landis, J.R., Koch, G.G., The measurement of observer agreement for categorical data (1977) Biometrics, 33, pp. 159-174
Keywords: Agreement; Apgar score; Cardiotocography; correlation coefficient; Female; Fetal Blood; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; intrapartum care; limit of agreement; newborn assessment; normal human; observer variation; Obstetrics; outcome variable; Pregnancy; Pregnancy Outcome; priority journal; reproducibility; Reproducibility of Results; review; statistical data interpretation; statistical parameters; Umbilical Arteries; Umbilical artery blood pH; umbilical cord blood

Low frame rate cell tracking: A Delaunay graph matching approach - Chen, Y.; Quelhas, P.; Campilho, A. (Proceedings - International Symposium on Biomedical ImagingIEEE Comput. Soc. Conf. Comput. Vis. Pattern Recogn., 2011)
Cell tracking is a fundamental problem for studying live cell dynamics. A novel approach for low frame rate cell tracking in fluorescent microscopy image is herein proposed. The method is based on sliding band filter detection and Delaunay triangulation sub-graph matching. With this approach we can track a large amount of small cells without their motion model and not relying on cell motion continuity between consecutive images. The effectiveness and robustness of the method were validated by visual inspection and on a ground truth dataset. © 2011 IEEE.
Conference code: 87101Export Date: 21 November 2012Source: ScopusArt. No.: 5872573doi: 10.1109/ISBI.2011.5872573Language of Original Document: EnglishCorrespondence Address: Chen, Y.; INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, 4150-180 Porto, PortugalReferences: Godinez, W.J., Lampe, M., Worz, S., Muller, B., Eils, R., Rohr, K., Tracking of virus particles in time-lapse fluorescence microscopy image sequences (2007) Proceedings of the IEEE International Symposium on Biomedical Imaging, pp. 256-259;Finch, A.W., Wilson, R.C., Hancock, E.R., Symbolic graph matching with the em algorithm (1998) Pattern Recognit, 31 (11), pp. 1777-1790. , Nov; Finch, M.A., Wilson, C.R., Hancock, R.E., Matching delaunay graphs (1997) Pattern Recognit, 30 (1), pp. 123-140. , Nov; Quelhas, P., Marcuzzo, M., Mendonça, A.M., Campilho, A., Cell nuclei and cytoplasm joint segmentation using the sliding band filter (2010) IEEE Transactions on Medical Imaging, 29, pp. 1463-1473; Fortune, S., A sweepline algorithm for voronoi diagram (1987) Algorithmica, 2, pp. 153-174; Khoo, K., Suganthan, P., Evaluation of genetic operators and solution representations for shape recognition by genetic algorithms (2002) Patt. Recognit. Lett., 23 (13), pp. 1589-1597; Caetano, T.S., Caelli, T., Schuurmans, D., Barone, D., Graphical models and point pattern matching (2006) IEEE Trans. on Pattern Analysis and Machine Intelligence, 28 (10), pp. 1646-1662. , Oct; Raveaux, R., Burie, J.-C., Ogier, J.-M., A graph matching method and a graph matching distance based on subgraph assignments (2010) Pattern Recognition Letters, 31, pp. 394-406; Marcuzzo, M., Quelhas, P., Campilho, A., Cell division detection on the arabidopsis thaliana root (2009) IbPRIA 2009, 5524, pp. 168-175. , LNCS Sponsors: Inst. Electr. Electron. Eng., Eng. Med. Biol. Soc. (IEEE EMBS); Inst. Electr. Electron. Eng., Signal Process. Soc. (IEEE SPS)
Keywords: Band filters; cell motion; Cell tracking; Cells; Consecutive images; Data sets; Delaunay graph; Delaunay graph matching; Delaunay triangulation; Fluorescent microscopy; Frame rate; Fundamental problem; Ground truth; Live cell; low frame rate tracking; Medical imaging; Motion models; small target tracking; Small targets; Target tracking; Visual inspection

MIQuant - semi-automation of infarct size assessment in models of cardiac ischemic injury - Nascimento, D.S.; Valente, M.; Esteves, T.; De Fátima De Pina, M.; Guedes, J.G.; Freire, A.; Quelhas, P.; Pinto-Do-Ó, P. (PLoS ONE, 2011)
Cited By (since 1996):1Export Date: 2 October 2013Source: ScopusArt. No.: e25045

Molecular recognition force spectroscopy: A new tool to tailor targeted nanoparticles - Oliveira, H.; Rangl, M.; Ebner, A.; Mayer, B.; Hinterdorfer, P.; Pêgo, A.P. (SmallSmall, 2011)
The density of targeting moieties in a nanoparticle-based gene-delivery system has been shown to play a fundamental role in its vectoring performance. Here, molecular recognition force spectroscopy is proposed as a novel screening tool to optimize the density of targeting moieties of functionalized nanoparticles towards attaining cell-specific interaction. By tailoring the nanoparticle formulation, the unbinding event probability between nanoparticles tethered to an atomic force microscopy tip and neuronal cells is directly correlated to the nanoparticle gene-vectoring capacity. Additionally, new insights into protein-receptor interaction are revealed. This novel approach opens new avenues in the field of nanomedicine. A novel screening tool is described to optimize the density of targeting moieties of functionalized nanoparticles towards attaining cell-specific interaction. The unbinding event probability between nanoparticles tethered to an atomic force microscopy tip and neuronal cells is directly correlated to the nanoparticle gene-vectoring capacity. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1002/smll.201002074Language of Original Document: EnglishCorrespondence Address: Pêgo, A. P.; INEB-Instituto de Engenharia Biomédica, Divis̃o de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptReferences: Verma, I.M., Weitzman, M.D., (2005) Annu. Rev. Biochem., 74, pp. 711-738;Midoux, P., Breuzard, G., Gomez, J.P., Pichon, C., (2008) Curr. Gene Ther., 8, pp. 335-352; Oliveira, H., Fernandez, R., Pires, L.R., Martins, M.C., Simoes, S., Barbosa, M.A., Pego, A.P., (2010) J. Controlled Release, 143, pp. 350-358; Hinterdorfer, P., Baumgartner, W., Gruber, H.J., Schilcher, K., Schindler, H., (1996) Proc. Natl. Acad. Sci. USA, 93, pp. 3477-3481; Ebner, A., Wildling, L., Kamruzzahan, A.S., Rankl, C., Wruss, J., Hahn, C.D., Holzl, M., Gruber, H.J., (2007) Bioconjugate Chem., 18, pp. 1176-1184; Fotinou, C., Emsley, P., Black, I., Ando, H., Ishida, H., Kiso, M., Sinha, K.A., Isaacs, N.W., (2001) J. Biol. Chem., 276, pp. 32274-32281; Ebner, A., Hinterdorfer, P., Gruber, H.J., (2007) Ultramicroscopy, 107, pp. 922-927; Baumgartner, W., Hinterdorfer, P., Schindler, H., (2000) Ultramicroscopy, 82, pp. 85-95; Evans, E., Ritchie, K., (1997) Biophys. J., 72, pp. 1541-1555; Evans, E., Ritchie, K., (1999) Biophys. J., 76, pp. 2439-2447; Bell, G.I., (1978) Science, 200, pp. 618-627; Sinha, K., Box, M., Lalli, G., Schiavo, G., Schneider, H., Groves, M., Siligardi, G., Fairweather, N., (2000) Mol. Microbiol., 37, pp. 1041-1051; Halpern, J.L., Loftus, A., (1993) J. Biol. Chem., 268, pp. 11188-11192; Owens III, D.E., Peppas, N.A., (2006) Int. J. Pharm., 307, pp. 93-102; Storm, G., Belliot, S.O., Daemen, T., Lasic, D.D., (1995) Adv. Drug Delivery Rev., 17, pp. 31-48; Gu, F., Zhang, L., Teply, B.A., Mann, N., Wang, A., Radovic-Moreno, A.F., Langer, R., Farokhzad, O.C., (2008) Proc. Natl. Acad. Sci. USA, 105, pp. 2586-2591; Butt, H.J., Jaschke, M., (1995) Nanotechnology, 6, pp. 1-7; Hutter, J.L., Bechhoefer, J., (1993) Rev. Sci. Instrum., 64, pp. 1868-1873; Rankl, C., Kienberger, F., Wildling, L., Wruss, J., Gruber, H.J., Blaas, D., Hinterdorfer, P., (2008) Proc. Natl. Acad. Sci. USA, 105, pp. 17778-17783
Keywords: article; Atomic force microscopy; Atomic spectroscopy; atomic-force microscopy; chemistry; Event probability; Force spectroscopy; Functionalized nanoparticles; gene technology; Gene-delivery systems; Genes; Medical nanotechnology; medicine; methodology; Microscopy, Atomic Force; Molecular biology; Molecular recognition; molecular recognition force spectroscopy; Nanomedicines; nanoparticle; Nanoparticle formulation; nanoparticles; Nanotechnology; Neuronal cell; Optimization; Receptor interaction; Screening tool; Specific interaction; Targeted nanoparticle

Molecularly designed alginate hydrogels susceptible to local proteolysis as three-dimensional cellular microenvironments - Fonseca, K.B.; Bidarra, S.J.; Oliveira, M.J.; Granja, P.L.; Barrias, C.C. (Acta BiomaterialiaActa Biomater., 2011)
The development of sophisticated three-dimensional (3-D) cell culture microenvironments that recreate some of the complexity of the natural extracellular matrix (ECM) remains a challenging task. Here, the modification of alginate through partial crosslinking with a matrix metalloproteinase (MMP) cleavable peptide (proline-valine-glycine-leucine-isoleucine-glycine, PVGLIG) is described, and its use in the preparation of injectable, in situ crosslinkable hydrogel-like matrices is proposed. PVGLIG-grafted alginates were synthesized by carbodiimide chemistry and characterized. Their biological performance was evaluated by comparing the response of 3-D cultured mesenchymal stem cells (MSCs) to alginate hydrogels containing only cell-adhesion peptides (RGD-alginate) or both peptides (PVGLIG/RGD-alginate). After 1 week, cells remained essentially round within RGD-alginate, while they exhibited an elongated morphology within PVGLIG/RGD-alginate hydrogels, forming cellular networks. This suggests that cells were able to structurally reorganize the matrix, through enzymatic hydrolysis of PVGLIG residues, overcoming biophysical hydrogel resistance. As shown by gelatine-zymography, MSC presented higher activity of MMP-2 when cultured within alginate functionalized with MMP-sensitive peptide, suggesting that the cell's proteolytic phenotype was modulated by the matrix composition. Additionally, PVGLIG/RGD-alginate hydrogels were clearly degraded in cell culture. Taken together, the results demonstrate that the co-incorporation of MMP-labile peptides in cell-adhesive RGD-alginate hydrogels improved their performance as ECM analogues, providing a more dynamic and physiological 3-D cellular microenvironment. © 2010 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2010.12.029PubMed ID: 21193068Language of Original Document: EnglishCorrespondence Address: Barrias, C. C.; INEB, Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade Do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; gelatin, 9000-70-8; gelatinase A, 146480-35-5; Alginates; Glucuronic Acid, 576-37-4; Hexuronic Acids; Hydrogels; Matrix Metalloproteinases, 3.4.24.-; Peptides; alginic acid, 9005-32-7References: Lukashev, M.E., Werb, Z., ECM signalling: Orchestrating cell behaviour and misbehaviour (1998) Trends in Cell Biology, 8 (11), pp. 437-441. , DOI 10.1016/S0962-8924(98)01362-2, PII S0962892498013622;Bosman, F.T., Stamenkovic, I., Functional structure and composition of the extracellular matrix (2003) Journal of Pathology, 200 (4), pp. 423-428. , DOI 10.1002/path.1437; Lutolf, M.P., Hubbell, J.A., Synthetic biomaterials as instructive extracellular microenvironments for morphogenesis in tissue engineering (2005) Nature Biotechnology, 23 (1), pp. 47-55. , DOI 10.1038/nbt1055; Lutolf, M.P., Gilbert, P.M., Blau, H.M., Designing materials to direct stem-cell fate (2009) Nature, 462 (7272), pp. 433-441; Tibbitt, M.W., Anseth, K.S., Hydrogels as extracellular matrix mimics for 3D cell culture (2009) Biotechnol Bioeng, 103 (4), pp. 655-663; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromolecular Bioscience, 6 (8), pp. 623-633. , DOI 10.1002/mabi.200600069; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.-J., Barrias, C.C., Salema, R., Granja, P.L., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28 (25), pp. 3644-3655. , DOI 10.1016/j.biomaterials.2007.04.028, PII S014296120700347X; Grellier, M., Granja, P.L., Fricain, J.C., Bidarra, S.J., Renard, M., Bareille, R., The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect (2009) Biomaterials, 30 (19), pp. 3271-3278; Bidarra, S.J., Barrias, C.C., Barbosa, M.A., Soares, R., Granja, P.L., Immobilization of human mesenchymal stem cells within RGD-grafted alginate microspheres and assessment of their angiogenic potential (2010) Biomacromolecules, 11 (8), pp. 1956-1964; West, J.L., Hubbell, J.A., Polymeric biomaterials with degradation sites for proteases involved in cell migration (1999) Macromolecules, 32 (1), pp. 241-244; Page-Mccaw, A., Ewald, A.J., Werb, Z., Matrix metalloproteinases and the regulation of tissue remodelling (2007) Nat Rev Mol Cell Biol, 8 (3), pp. 221-233; Murphy, G., Nagase, H., Progress in matrix metalloproteinase research (2008) Mol Aspects Med, 29 (5), pp. 290-308; Chau, Y., Luo, Y., Cheung, A.C.Y., Nagai, Y., Zhang, S., Kobler, J.B., Incorporation of a matrix metalloproteinase-sensitive substrate into self-assembling peptides - A model for biofunctional scaffolds (2008) Biomaterials, 29 (11), pp. 1713-1719; Chau, Y., Tan, F.E., Langer, R., Synthesis and characterization of dextran-peptide-methotrexate conjugates for tumor targeting via mediation by matrix metalloproteinase II and matrix metalloproteinase IX (2004) Bioconjugate Chemistry, 15 (4), pp. 931-941. , DOI 10.1021/bc0499174; Turk, B.E., Huang, L.L., Piro, E.T., Cantley, L.C., Determination of protease cleavage site motifs using mixture-based oriented peptide libraries (2001) Nature Biotechnology, 19 (7), pp. 661-667. , DOI 10.1038/90273; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029. , DOI 10.1016/S0142-9612(03)00295-3; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20 (1), pp. 45-53. , DOI 10.1016/S0142-9612(98)00107-0, PII S0142961298001070; Lorenzen, A., Kennedy, S.W., A fluorescence-based protein assay for use with a microplate reader (1993) Analytical Biochemistry, 214 (1), pp. 346-348. , DOI 10.1006/abio.1993.1504; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering: Part 1. Structure, gelation rate and mechanical properties (2001) Biomaterials, 22 (6), pp. 511-521. , DOI 10.1016/S0142-9612(00)00201-5, PII S0142961200002015; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Pena Ferreira, M.R., Bahia, M.F., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability (2008) J Biomed Mater Res B Appl Biomater, 87 (1), pp. 49-58; Kavimandan, N.J., Losi, E., Wilson, J.J., Brodbelt, J.S., Peppas, N.A., Synthesis and characterization of insulin-transferrin conjugates (2006) Bioconjugate Chemistry, 17 (6), pp. 1376-1384. , DOI 10.1021/bc050344k; Lee, K.Y., Rowley, J.A., Eiselt, P., Moy, E.M., Bouhadir, K.H., Mooney, D.J., Controlling mechanical and swelling properties of alginate hydrogels independently by cross-linker type and cross-linking density (2000) Macromolecules, 33 (11), pp. 4291-4294; Dent, A., Aslam, M., The functional chemistry of proteins and protein coupling (1998) Bioconjugation: Protein Coupling Techniques for the Biomedical Sciences, pp. 50-100; Werb, Z., ECM and cell surface proteolysis: Regulating cellular ecology (1997) Cell, 91 (4), pp. 439-442; Friedl, P., Brocker, E.-B., The biology of cell locomotion within three-dimensional extracellular matrix (2000) Cellular and Molecular Life Sciences, 57 (1), pp. 41-64. , DOI 10.1007/s000180050498; Drury, J.L., Boontheeku, T., Mooney, D.J., Cellular cross-linking of peptide modified hydrogels (2005) Journal of Biomechanical Engineering, 127 (2), pp. 220-228. , DOI 10.1115/1.1865194; Boontheekul, T., Kong, H.-J., Mooney, D.J., Controlling alginate gel degradation utilizing partial oxidation and bimodal molecular weight distribution (2005) Biomaterials, 26 (15), pp. 2455-2465. , DOI 10.1016/j.biomaterials.2004.06.044, PII S0142961204006064; Ries, C., Egea, V., Karow, M., Kolb, H., Jochum, M., Neth, P., MMP-2, MT1-MMP, and TIMP-2 are essential for the invasive capacity of human mesenchymal stem cells: Differential regulation by inflammatory cytokines (2007) Blood, 109 (9), pp. 4055-4063. , http://bloodjournal.hematologylibrary.org/cgi/reprint/109/9/4055, DOI 10.1182/blood-2006-10-051060; Seiki, M., The cell surface: The stage for matrix metalloproteinase regulation of migration (2002) Current Opinion in Cell Biology, 14 (5), pp. 624-632. , DOI 10.1016/S0955-0674(02)00363-0; Will, H., Atkinson, S.J., Butler, G.S., Smith, B., Murphy, G., The soluble catalytic domain of membrane type 1 matrix metalloproteinase cleaves the propeptide of progelatinase A and initiates autoproteolytic activation. Regulation by TIMP-2 and TIMP-3 (1996) Journal of Biological Chemistry, 271 (29), pp. 17119-17123. , DOI 10.1074/jbc.271.29.17119; Itoh, Y., Seiki, M., MT1-MMP: A potent modifier of pericellular microenvironment (2006) Journal of Cellular Physiology, 206 (1), pp. 1-8. , DOI 10.1002/jcp.20431; Barbolina, M.V., Adley, B.P., Ariztia, E.V., Liu, Y., Stack, M.S., Microenvironmental regulation of membrane type 1 matrix metalloproteinase activity in ovarian carcinoma cells via collagen-induced EGR1 expression (2007) Journal of Biological Chemistry, 282 (7), pp. 4924-4931. , http://www.jbc.org/cgi/reprint/282/7/4924, DOI 10.1074/jbc.M608428200
Keywords: 3-D Cell culture; Alginate; Alginates; alginic acid; Amino Acid Sequence; article; cell adhesion; cell composition; Cell Count; Cell culture; Cell Culture Techniques; Cell Shape; cell structure; cell survival; cell viability; Cells, Cultured; controlled study; Enzyme Activation; enzyme activity; extracellular matrix; Extracellular matrix (ECM); gelatin; gelatinase A; Glucuronic Acid; Hexuronic Acids; human; human cell; Humans; hydrogel; Hydrogels; hydrolysis; matrix metalloproteinase; Matrix Metalloproteinases; Matrix metalloproteinases (MMPs); Mesenchymal stem cell; Mesenchymal Stem Cells; Molecular Sequence Data; morphology; peptide derivative; Peptides; phenotype; priority journal; prolylvalylglycylleucylisoleucylglycine; Protease-sensitive; protein cleavage; protein degradation; Protein Processing, Post-Translational; Subcellular Fractions; tumor microenvironment; unclassified drug; zymography

New results on minimum error entropy decision trees - De Sá, J.P.M.; Sebastião, R.; Gama, J.; Fontes, T. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2011)
We present new results on the performance of Minimum Error Entropy (MEE) decision trees, which use a novel node split criterion. The results were obtained in a comparive study with popular alternative algorithms, on 42 real world datasets. Carefull validation and statistical methods were used. The evidence gathered from this body of results show that the error performance of MEE trees compares well with alternative algorithms. An important aspect to emphasize is that MEE trees generalize better on average without sacrifing error performance. © 2011 Springer-Verlag.
Conference code: 87418Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-25085-9_42Language of Original Document: EnglishCorrespondence Address: De Sá, J.P.M.; INEB-Instituto de Engenharia Biomédica, FEUP, Universidade Do Porto, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: jmsa@fe.up.ptReferences: Rokach, L., Maimon, O., Decision Trees (2005) Data Mining and Knowledge Discovery Handbook, , Maimon, O., Rokach, L. (eds.) Springer, Heidelberg;Marques De Sá, J.P., Sebastião, R., Gama, J., Tree Classifiers Based on Minimum Error Entropy Decisions (2011) Can. J. Artif. Intell., Patt. Rec. and Mach. Learning, , in press; Silva, L., Felgueiras, C.S., Alexandre, L., Marques De Sá, J., Error Entropy in Classification Problems: A Univariate Data Analysis (2006) Neural Computation, 18, pp. 2036-2061; Asuncion, A., Newman, D.J., (2010) UCI Machine Learning Repository, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Kearns, M., A Bound on the Error of Cross Validation Using the Approximation and Estimation Rates, with Consequences for the Training-Test Split (1997) Neural Computation, 9, pp. 1143-1161; Molinaro, A.M., Simon, R., Pfeiffer, R.M., Prediction Error Estimation: A Comparison of Resampling Methods (2005) Bioinformatics, 21, pp. 3301-3307; Demšar, J., Statistical Comparisons of Classifiers over Multiple Data Sets (2006) J. of Machine Learning Research, 7, pp. 1-30; García, S., Fernández, A., Luengo, J., Herrera, F., Advanced Nonparametric Tests for Multiple Comparisons in the Design of Experiments in Computational Intelligence and Data Mining: Experimental Analysis of Power (2010) Information Sciences, 180, pp. 2044-2064; Hochberg, Y., Tamhane, A.C., (1987) Multiple Comparison Procedures, , John Wiley & Sons, Inc; Salzberg, S.L., On Comparing Classifiers: Pitfalls to Avoid and a Recommended Approach (1997) Data Mining and Knowledge Discovery, 1, pp. 317-328; Jensen, D., Oates, T., Cohen, P.R., Building Simple Models: A Case Study with Decision Trees (1997) LECTURE NOTES IN COMPUTER SCIENCE, (1280), pp. 211-222. , Advances in Intelligent Data Analysis Reasoning about Data; Li, R.-H., Belford, G.G., Instability of Decision Tree Classification Algorithms (2002) Proc. 8th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining, pp. 570-575 Sponsors: Universidad de La Frontera (UFRO); The International Association for Pattern Recognition (IAPR); Asociacon Chilena de Reconocimiento de Patrones (AChiRP); Asociacion Cubana de Reconocimiento de Patrones (ACPR); Mex. Assoc. Comput. Vis., Neural Comput. Rob. (MACVNR)
Keywords: Algorithms; Alternative algorithms; Computer vision; Decision Theory; decision trees; entropy; entropy-of-error; Error entropy; Error performance; Forestry; New results; node split criteria; Real-world datasets; Vision

Non-viral gene delivery to mesenchymal stem cells: Methods, strategies and application in bone tissue engineering and regeneration - Santos, J.L.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Current Gene TherapyCurr. Gene Ther., 2011)
Mesenchymal stem cells (MSCs) can be isolated from several tissues in the body, have the ability to selfrenewal, show immune suppressive properties and are multipotent, being able to generate various cell types. At present, due to their intrinsic characteristics, MSCs are considered very promising in the area of tissue engineering and regenerative medicine. In this context, genetic modification can be a powerful tool to control the behavior and fate of these cells and be used in the design of new cellular therapies. Viral systems are very effective in the introduction of exogenous genes inside MSCs. However, the risks associated with their use are leading to an increasing search for non-viral approaches to attain the same purpose, even if MSCs have been shown to be more difficult to transfect in this way. In the past few years, progress was made in the development of chemical and physical methods for non-viral gene delivery. Herein, an overview of the application of those methods specifically to MSCs is given and their use in tissue engineering and regenerative medicine therapeutic strategies highlighted using the example of bone tissue. Key issues and future directions in non-viral gene delivery to MSCs are also critically addressed. © 2011 Bentham Science Publishers Ltd.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: CGTUAdoi: 10.2174/156652311794520102PubMed ID: 21182464Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM-Centro de Química da Madeira, MMRG, Universidade da Madeira, Campus Universitário da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptReferences: Bianco, P., Robey, P.G., Simmons, P.J., Mesenchymal stem cells: Revisitinghistory, concepts, and assays (2008) Cell Stem Cell, 2, pp. 313-319;Marot, D., Knezevic, M., Novakovic, G.V., Bone tissue engineeringwith human stem cells (2010) Stem Cell Res Ther, 1, p. 10; Caplan, A.I., Review: Mesenchymal stem cells: Cell-based reconstructivetherapy in orthopedics (2005) Tissue Eng, 11, pp. 1198-1211; Caplan, A.I., Bruder, S.P., Mesenchymal stem cells: Building blocksfor molecular medicine in the 21st century (2001) Trends Mol Med, 7, pp. 259-264; Chen, F.H., Tuan, R.S., Mesenchymal stem cells in arthritic diseases (2008) Arthritis Res Ther, 10, p. 223; Da Silva Meirelles, L., Chagastelles, P.C., Nardi, N.B., Mesenchymalstem cells reside in virtually all post-natal organs and tissues (2006) J CellSci, 119, pp. 2204-2213; Mauney, J.R., Volloch, V., Kaplan, D.L., Role of adult mesenchymalstem cells in bone tissue engineering applications: Current statusand future prospects (2005) Tissue Eng, 11, pp. 787-802; Prockop, D.J., Repair of tissues by adult stem/progenitor cells(MSCs): Controversies, myths, and changing paradigms (2009) Mol Ther, 17, pp. 939-946; Sakurada, K., McDonald, F.M., Shimada, F., Regenerative medicineand stem cell based drug discovery (2008) Angew Chem Int Ed Engl, 47, pp. 5718-5738; Väänänen, H.K., Mesenchymal stem cells (2005) Ann Med, 37, pp. 469-479; Jackson, W.M., Nesti, L.J., Tuan, R.S., Potential therapeutic applicationsof muscle-derived mesenchymal stem and progenitor cells (2010) ExpertOpin Biol Ther, 10, pp. 505-517; Nauta, A.J., Fibbe, W.E., Immunomodulatory properties of mesenchymalstromal cells (2007) Blood, 110, pp. 3499-3506; Heyde, M., Partridge, K.A., Oreffo, R.O., Gene therapy used fortissue engineering applications (2007) J Pharm Pharmacol, 59, pp. 329-350; Kimelman, N., Pelled, G., Helm, G.A., Review: Gene-and stemcell-based therapeutics for bone regeneration and repair (2007) TissueEng, 13, pp. 1135-1150; Partridge, K.A., Oreffo, R.O., Gene delivery in bone tissue engineering: Progress and prospects using viral and nonviral strategies (2004) TissueEng, 10, pp. 295-307; Pittenger, M., Vanguri, P., Simonetti, D., Adult mesenchymalstem cells: Potential for muscle and tendon regeneration and use ingene therapy (2002) J Musculoskelet Neuronal Interact, 2, pp. 309-320; Reiser, J., Zhang, X.Y., Hemenway, C.S., Potential of mesenchymalstem cells in gene therapy approaches for inherited and acquireddiseases (2005) Expert Opin Biol Ther, 5, pp. 1571-1584; Saraf, A., Mikos, A.G., Gene delivery strategies for cartilage tissueengineering (2006) Adv Drug Deliv Rev, 58, pp. 592-603; Trippel, S.B., Ghivizzani, S.C., Nixon, A.J., Gene-based approaches forthe repair of articular cartilage (2004) Gene Ther, 11, pp. 351-359; Takahashi, K., Yamanaka, S., Induction of pluripotent stem cells frommouse embryonic and adult fibroblast cultures by defined factors (2006) Cell, 126, pp. 663-676; Yu, J., Vodyanik, M.A., Smuga-Otto, K., Induced pluripotentstem cell lines derived from human somatic cells (2007) Science, 318, pp. 1917-1920; Steinert, A.F., Noth, U., Tuan, R.S., Concepts in gene therapy for cartilagerepair (2008) Injury, 39 (SUPPL 1), pp. S97-S113; Gafni, Y., Turgeman, G., Liebergal, M., Stem cells as vehiclesfor orthopedic gene therapy (2004) Gene Ther, 11, pp. 417-426; Kane, N.M., McRae, S., Denning, C., Viral and non-viral genedelivery and its role in pluripotent stem cell engineering Drug DiscovToday: Technol, , In press. doi:10.1016/j.ddtec.2008.10.002; Li, S.D., Huang, L., Non-viral is superior to viral gene delivery (2007) JControl Release, 123, pp. 181-183; Mastrobattista, E., Bravo, S.A., van der Aa, M., Nonviral genedelivery systems: From simple transfection agents to artificial viruses (2005) Drug Discov Today: Technol, 2, pp. 103-109; Chan, J., O'Donoghue, K., de la Fuente, J., Human fetal mesenchymalstem cells as vehicles for gene delivery (2005) Stem Cells, 23, pp. 93-102; Tsuda, H., Wada, T., Yamashita, T., Enhanced osteoinduction bymesenchymal stem cells transfected with a fiber-mutant adenoviralBMP2 gene (2005) J Gene Med, 7, pp. 1322-1334; Zhang, X., Godbey, W.T., Viral vectors for gene delivery in tissueengineering (2006) Adv Drug Deliv Rev, 58, pp. 515-534; Dang, J.M., Leong, K.W., Natural polymers for gene delivery and tissue engineering (2006) Adv Drug Deliv Rev, 58, pp. 487-499; Luten, J., van Nostrum, C.F., De Smedt, S.C., Biodegradablepolymers as non-viral carriers for plasmid DNA delivery (2008) J ControlRelease, 126, pp. 97-110; Mintzer, M.A., Simanek, E.E., Nonviral vectors for gene delivery (2009) Chem Rev, 109, pp. 259-302; Panyam, J., Labhasetwar, V., Biodegradable nanoparticles for drugand gene delivery to cells and tissue (2003) Adv Drug Deliv Rev, 55, pp. 329-347; Choi, J.S., Ko, K.S., Park, J.S., Dexamethasone conjugatedpoly(amidoamine) dendrimer as a gene carrier for efficient nucleartranslocation (2006) Int J Pharm, 320, pp. 171-178; Roth, C.M., Sundaram, S., Engineering synthetic vectors for improvedDNA delivery: Insights from intracellular pathways (2004) Annu RevBiomed Eng, 6, pp. 397-426; Wood, K.C., Little, S.R., Langer, R., A family of hierarchicallyself-assembling linear-dendritic hybrid polymers for highly efficienttargeted gene delivery (2005) Angew Chem Int Ed Engl, 44, pp. 6704-6708; Mehier-Humbert, S., Guy, R.H., Physical methods for gene transfer: Improving the kinetics of gene delivery into cells (2005) Adv Drug DelivRev, 57, pp. 733-753; Jo, J., Tabata, Y., Non-viral gene transfection technologies for geneticengineering of stem cells (2008) Eur J Pharm Biopharm, 68, pp. 90-104; Song, L., Chau, L., Sakamoto, Y., Electric field-induced molecularvibration for noninvasive, high-efficiency DNA transfection (2004) Mol Ther, 9, pp. 607-616; Han, S.W., Nakamura, C., Kotobuki, N., High-efficiency DNAinjection into a single human mesenchymal stem cell using ananoneedle and atomic force microscopy (2008) Nanomedicine, 4, pp. 215-225; Park, S., Kim, Y.S., Kim, W.B., Carbon nanosyringe array as aplatform for intracellular delivery (2009) Nano Lett, 9, pp. 1325-1329; Durieux, A.C., Bonnefoy, R., Busso, T., In vivo gene electrotransferinto skeletal muscle: Effects of plasmid DNA on the occurrenceand extent of muscle damage (2004) J Gene Med, 6, pp. 809-816; Winn, S.R., Hu, Y., Sfeir, C., Gene therapy approaches for modulatingbone regeneration (2000) Adv Drug Deliv Rev, 42, pp. 121-138; Lv, H., Zhang, S., Wang, B., Toxicity of cationic lipids and cationicpolymers in gene delivery (2006) J Control Release, 114, pp. 100-109; Gebhart, C.L., Kabanov, A.V., Evaluation of polyplexes as gene transferagents (2001) J Control Release, 73, pp. 401-416; Hamm, A., Krott, N., Breibach, I., Efficient transfection methodfor primary cells (2002) Tissue Eng, 8, pp. 235-245; Gill, D.R., Pringle, I.A., Hyde, S.C., Progress and prospects: The designand production of plasmid vectors (2009) Gene Ther, 16, pp. 165-171; Miller, A.M., Dean, D.A., Tissue-specific and transcription factormediatednuclear entry of DNA (2009) Adv Drug Deliv Rev, 61, pp. 603-613; Smith, D.K., Dendrimers and the double helix--from DNA bindingtowards gene therapy (2008) Curr Top Med Chem, 8, pp. 1187-1203; Duzgunes, N., De Ilarduya, C.T., Simoes, S., Cationic liposomesfor gene delivery: Novel cationic lipids and enhancement by proteinsand peptides (2003) Curr Med Chem, 10, pp. 1213-1220; Hoekstra, D., Rejman, J., Wasungu, L., Gene delivery by cationiclipids: In and out of an endosome (2007) Biochem Soc Trans, 35, pp. 68-71; Hoelters, J., Ciccarella, M., Drechsel, M., Nonviral genetic modificationmediates effective transgene expression and functionalRNA interference in human mesenchymal stem cells (2005) J Gene Med, 7, pp. 718-728; Ko, B.S., Chang, T.C., Shyue, S.K., An efficient transfectionmethod for mouse embryonic stem cells (2009) Gene Ther, 16, pp. 154-158; Park, J., Lutz, R., Felszeghy, E., The effect on bone regenerationof a liposomal vector to deliver BMP-2 gene to bone grafts in periimplantbone defects (2007) Biomaterials, 28, pp. 2772-2782; Park, J., Ries, J., Gelse, K., Bone regeneration in critical sizedefects by cell-mediated BMP-2 gene transfer: A comparison of adenoviral vectors and liposomes (2003) Gene Ther, 10, pp. 1089-1098; Vanderbyl, S., McDonald, G.N., Sidhu, S., Transfer and stabletransgene expression of a mammalian artificial chromosome intobone marrow-derived human mesenchymal stem cells (2004) Stem Cells, 22, pp. 324-333; de Jong, G., Telenius, A., Vanderbyl, S., Efficient in-vitro transferof a 60-Mb mammalian artificial chromosome into murine and hamster cells using cationic lipids and dendrimers (2001) ChromosomeRes, 9, pp. 475-485; Dass, C.R., Cytotoxicity issues pertinent to lipoplex-mediated genetherapy in-vivo (2002) J Pharm Pharmacol, 54, pp. 593-601; Wu, G.Y.W.C., Receptor-mediated in vitro gene transformation by asoluble DNA carrier system (1987) J Biol Chem, 262, pp. 4429-4432; Choi, Y.H., Liu, F., Kim, J.S., Polyethylene glycol-grafted poly-Llysineas polymeric gene carrier (1998) J Control Release, 54, pp. 39-48; Liu, G., Molas, M., Grossmann, G.A., Biological properties of poly-L-lysine-DNA complexes generated by cooperative binding of the polycation (2001) J Biol Chem, 276, pp. 34379-34387; Farrell, L.L., Pepin, J., Kucharski, C., A comparison of the effectivenessof cationic polymers poly-L-lysine (PLL) and polyethylenimine(PEI) for non-viral delivery of plasmid DNA to bone marrowstromal cells (BMSC) (2007) Eur J Pharm Biopharm, 65, pp. 388-397; Incani, V., Tunis, E., Clements, B.A., Palmitic acid substitutionon cationic polymers for effective delivery of plasmid DNA tobone marrow stromal cells (2007) J Biomed Mater Res A, 81, pp. 493-504; Clements, B.A., Incani, V., Kucharski, C., A comparative evaluationof poly-L-lysine-palmitic acid and Lipofectamine 2000 forplasmid delivery to bone marrow stromal cells (2007) Biomaterials, 28, pp. 4693-4704; Bragonzi, A., Boletta, A., Biffi, A., Comparison between cationicpolymers and lipids in mediating systemic gene delivery to thelungs (1999) Gene Ther, 6, pp. 1995-2004; Sea, F., Exgen 500 is an efficient vector for gene delivery tolung epithelial cells in vitro and in vivo (1997) Gene Ther, 4, pp. 1100-1106; Wightman, L., Kircheis, R., Rossler, V., Different behavior of branched and linear polyethylenimine for gene delivery in vitro and in vivo (2001) J Gene Med, 3, pp. 362-372; Behr, J.-P., The Proton Sponge: A Trick to Enter Cells the VirusesDid Not Exploit (1997) Chimia, 51, pp. 34-36; Dea, F., A novel non-viral vector for DNA delivery based onlow molecular weight, branched polyethylenimine: Effect of molecularweight on transfection efficiency and cytotoxicity (1999) Pharm. Res, 16, pp. 1273-1279; Godbey, W.T., Wu, K.K., Mikos, A.G., Size matters: Molecular weightaffects the efficiency of poly(ethylenimine) as a gene delivery vehicle (1999) J Biomed Mater Res, 45, pp. 268-275; Ahn, H.H., Lee, M.S., Cho, M.H., DNA/PEI nano-particles forgene delivery of rat bone marrow stem cells (2008) Colloids and SurfacesA: Physicochem Eng Aspects, 313-314, pp. 116-120; Ahn, H.H., Lee, J.H., Kim, K.S., Polyethyleneimine-mediated genedelivery into human adipose derived stem cells (2008) Biomater, 29, pp. 2415-2422; Clements, B.A., Bai, J., Kucharski, C., RGD conjugation to polyethyleneiminedoes not improve DNA delivery to bone marrowstromal cells (2006) Biomacromolecules, 7, pp. 1481-1488; Saraf, A., Hacker, M.C., Sitharaman, B., Synthesis and conformationalevaluation of a novel gene delivery vector for human mesenchymalstem cells (2008) Biomacromolecules, 9, pp. 818-827; Lei, Y., Segura, T., DNA delivery from matrix metalloproteinasedegradable poly(ethylene glycol) hydrogels to mouse cloned mesenchymalstem cells (2009) Biomaterials, 30, pp. 254-265; Gwak, S.J., Kim, B.S., Poly(lactic-co-glycolic acid) nanosphere as avehicle for gene delivery to human cord blood-derived mesenchymalstem cells: Comparison with polyethylenimine (2008) Biotechnol Lett, 30, pp. 1177-1182; Yang, F., Green, J.J., Dinio, T., Gene delivery to human adult and embryonic cell-derived stem cells using biodegradable nanoparticulatepolymeric vectors (2009) Gene Ther, 16, pp. 533-546; Huang, M., Fong, C.W., Khor, E., Transfection efficiency of chitosan vectors: Effect of polymer molecular weight and degree of deacetylation (2005) J Control Release, 106, pp. 391-406; Ishii, T., Okahata, Y., Sato, T., Mechanism of cell transfection withplasmid/chitosan complexes (2001) Biochim Biophys Acta, 1514, pp. 51-64; Moreira, C., Oliveira, H., Pires, L.R., Improving chitosanmediatedgene transfer by the introduction of intracellular bufferingmoieties into the chitosan backbone (2009) Acta Biomater, 5, pp. 2995-3006; Sato, T., Ishii, T., Okahata, Y., In vitro gene delivery mediated bychitosan. effect of pH, serum, and molecular mass of chitosan onthe transfection efficiency (2001) Biomaterials, 22, pp. 2075-2080; Corsi, K., Chellat, F., Yahia, L., Mesenchymal stem cells, MG63and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24, pp. 1255-1264; Nie, H., Wang, C.H., Fabrication and characterization of PLGA/HApcomposite scaffolds for delivery of BMP-2 plasmid DNA (2007) J ControlRelease, 120, pp. 111-121; Hu, Y., Cai, K., Luo, Z., Surface mediated in situ differentiationof mesenchymal stem cells on gene-functionalized titanium filmsfabricated by layer-by-layer technique (2009) Biomaterials, 30, pp. 3626-3635; Okazaki, A., Jo, J., Tabata, Y., A reverse transfection technology togenetically engineer adult stem cells (2007) Tissue Eng, 13, pp. 245-251; Hosseinkhani, H., Azzam, T., Kobayashi, H., Combination of 3Dtissue engineered scaffold and non-viral gene carrier enhance in vitroDNA expression of mesenchymal stem cells (2006) Biomaterials, 27, pp. 4269-4278; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Enhanced ectopicbone formation using a combination of plasmid DNA impregnationinto 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Dufès, C., Uchegbu, I.F., Schätzlein, A.G., Dendrimers in gene delivery (2005) Adv Drug Deliv Rev, 57, pp. 2177-2202; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications--reflections on the field (2005) Adv Drug Deliv Rev, 57, pp. 2106-2129; Malik, N., Wiwattanapatapee, R., Klopsch, R., Dendrimers: Relationshipbetween structure and biocompatibility in vitro, and preliminarystudies on the biodistribution of 125I-labelled polyamidoaminedendrimers in vivo (2000) J Control Release, 65, pp. 133-148; Duncan, R., Izzo, L., Dendrimer biocompatibility and toxicity (2005) AdvDrug Deliv Rev, 57, pp. 2215-2237; Dennig, J., Duncan, E., Gene transfer into eukaryotic cells usingactivated polyamidoamine dendrimers (2002) J Biotechnol, 90, pp. 339-347; Sokolova, V.V., Radtke, I., Heumann, R., Effective transfection of cells with multi-shell calcium phosphate-DNA nanoparticles (2006) Biomaterials, 27, pp. 3147-3153; Santos, J.L., Oramas, E., Pego, A.P., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene deliveryvectors (2009) J Control Release, 134, pp. 141-148; Gheisari, Y., Soleimani, M., Azadmanesh, K., Multipotent mesenchymalstromal cells: Optimization and comparison of five cationicpolymer-based gene delivery methods (2008) Cytotherapy, 10, pp. 815-823; Holladay, C., Keeney, M., Greiser, U., A matrix reservoir forimproved control of non-viral gene delivery (2009) J Control Release, 136, pp. 220-225; Parekh, H.S., The advance of dendrimers-a versatile targeting platformfor gene/drug delivery (2007) Curr Pharm Des, 13, pp. 2837-2850; Santos, J.L., Pandita, D., Rodrigues, J., Receptor-mediated genedelivery using PAMAM dendrimers conjudated with peptides recognizedby mesenchymal stem cells (2010) Mol Pharmaceutics, 7, pp. 763-774; Santos, J.L., Oliveira, H., Pandita, D., Rodrigues, J., Functionalizationof Poly(amidoamine) Dendrimers with hydrophobic chains forimproved gene delivery in mesenchymal stem cells (2010) J Control Release, 144, pp. 55-64; Bourgeat-Lami, E., Organic-inorganic nanostructured colloids (2002) JNanosci Nanotechnol, 2, pp. 1-24; Chowdhury, E.H., Akaike, T., Bio-functional inorganic materials: Anattractive branch of gene-based nano-medicine delivery for 21stcentury (2005) Curr Gene Ther, 5, pp. 669-676; Sokolova, V., Epple, M., Inorganic nanoparticles as carriers of nucleicacids into cells (2008) Angew Chem Int Ed Engl, 47, pp. 1382-1395; Uchimura, E., Yamada, S., Uebersax, L., Method for reversetransfection using gold colloid as a nano-scaffold (2007) J Biosci Bioeng, 103, pp. 101-103; Gonzalez-McQuire, R., Green, D.W., Partridge, K.A., Coating of human mesenchymal cells in 3D culture with bioinorganicnanoparticles promotes osteoblastic differentiation and gene transfection (2007) Adv Mater, 19, pp. 2236-2240; Park, J.S., Na, K., Woo, D.G., Non-viral gene delivery of DNApolyplexed with nanoparticles transfected into human mesenchymalstem cells (2010) Biomaterials, 31, pp. 124-132; Peister, A., Mellad, J.A., Wang, M., Stable transfection of MSCsby electroporation (2004) Gene Ther, 11, pp. 224-228; Ferreira, E., Potier, E., Logeart-Avramoglou, D., Optimization of a gene electrotransfer method for mesenchymal stem cell transfection (2008) Gene Ther, 15, pp. 537-544; Ziv, R., Steinhardt, Y., Pelled, G., Micro-electroporation of mesenchymalstem cells with alternating electrical current pulses (2009) BiomedMicrodevices, 11, pp. 95-101; Lim, J.Y., Park, S.H., Jeong, C.H., Microporation is a valuabletransfection method for efficient gene delivery into human umbilicalcord blood-derived mesenchymal stem cells (2010) BMC Biotechnol, 10, p. 38; Lee, S.-J., Kang, S.-W., Do, H.-J., Enhancement of bone regenerationby gene delivery of BMP2/Runx2 bicistronic vector into adipose-derived stromal cells (2010) Biomater, 31, pp. 5652-5659; Lakshmipathy, U., Pelacho, B., Sudo, K., Efficient transfection of embryonic and adult stem cells (2004) Stem Cells, 22, pp. 531-543; Aluigi, M., Fogli, M., Curti, A., Nucleofection is an efficientnonviral transfection technique for human bone marrow-derivedmesenchymal stem cells (2006) Stem Cells, 24, pp. 454-461; Nakashima, S., Matsuyama, Y., Nitta, A., Highly efficient transfectionof human marrow stromal cells by nucleofection (2005) TransplantProc, 37, pp. 2290-2292; Miller, D.L., Pislaru, S.V., Greenleaf, J.E., Sonoporation: MechanicalDNA delivery by ultrasonic cavitation (2002) Somat Cell Mol Genet, 27, pp. 115-134; Otani, K., Yamahara, K., Ohnishi, S., Nonviral delivery of siRNA into mesenchymal stem cells by a combination of ultrasoundand microbubbles (2009) J Control Release, 133, pp. 146-153; Aslan, H., Sheyn, D., Gazit, D., Genetically engineered mesenchymalstem cells: Applications in spine therapy (2009) Regen Med, 4, pp. 99-108; Chiang, G.G., Rubin, H.L., Cherington, V., Bone marrow stromalcell-mediated gene therapy for hemophilia A: In vitro expression of human factor VIII with high biological activity requires the inclusionof the proteolytic site at amino acid 1648 (1999) Hum Gene Ther, 10, pp. 61-76; Gelse, K., von der Mark, K., Schneider, H., Cartilage regeneration bygene therapy (2003) Curr Gene Ther, 3, pp. 305-317; Moutsatsos, I.K., Turgeman, G., Zhou, S., Exogenously regulatedstem cell-mediated gene therapy for bone regeneration (2001) Mol Ther, 3, pp. 449-461; Phillips, M.I., Tang, Y.L., Genetic modification of stem cells for transplantation (2008) Adv Drug Deliv Rev, 60, pp. 160-172; Schwarz, E.J., Reger, R.L., Alexander, G.M., Rat marrow stromalcells rapidly transduced with a self-inactivating retrovirus synthesizeL-DOPA in vitro (2001) Gene Ther, 8, pp. 1214-1223; Sun, M., Kong, L., Wang, X., Coexpression of tyrosine hydroxylase, GTP cyclohydrolase I, aromatic amino acid decarboxylase, and vesicular monoamine transporter 2 from a helper virus-freeherpes simplex virus type 1 vector supports high-level, long-termbiochemical and behavioral correction of a rat model of Parkinson'sdisease (2004) Hum Gene Ther, 15, pp. 1177-1196; Turgeman, G., Pittman, D.D., Muller, R., Engineered humanmesenchymal stem cells: A novel platform for skeletal cell mediatedgene therapy (2001) J Gene Med, 3, pp. 240-251; Tuszynski, M.H., Thal, L., Pay, M., A phase 1 clinical trial of nerve growth factor gene therapy for Alzheimer disease (2005) Nat Med, 11, pp. 551-555; Fang, J., Zhu, Y.Y., Smiley, E., Stimulation of new bone formationby direct transfer of osteogenic plasmid genes (1996) Proc Natl AcadSci U S A, 93, pp. 5753-5758; Bonadio, J., Smiley, E., Patil, P., Localized, direct plasmid genedelivery in vivo: Prolonged therapy results in reproducible tissueregeneration (1999) Nat Med, 5, pp. 753-759; Kasper, F.K., Young, S., Tanahashi, K., Evaluation of bone regenerationby DNA release from composites of oligo(poly(ethyleneglycol) fumarate) and cationized gelatin microspheres in a criticalsizedcalvarial defect (2006) J Biomed Mater Res A, 78, pp. 335-342; Kuroda, S., Kondo, H., Ohya, K., A new technique with calciumphosphate precipitate enhances efficiency of in vivo plasmid DNAgene transfer (2005) J Pharmacol Sci, 97, pp. 227-233; Endo, M., Kuroda, S., Kondo, H., Bone regeneration by modifiedgene-activated matrix: Effectiveness in segmental tibial defects inrats (2006) Tissue Eng, 12, pp. 489-497; Huang, Y.C., Simmons, C., Kaigler, D., Bone regeneration in a ratcranial defect with delivery of PEI-condensed plasmid DNA encodingfor bone morphogenetic protein-4 (BMP-4) (2005) Gene Ther, 12, pp. 418-426; Nie, H., Ho, M.L., Wang, C.K., BMP-2 plasmid loadedPLGA/HAp composite scaffolds for treatment of bone defects innude mice (2009) Biomaterials, 30, pp. 892-901; Ono, I., Yamashita, T., Jin, H.Y., Combination of porous hydroxyapatiteand cationic liposomes as a vector for BMP-2 genetherapy (2004) Biomaterials, 25, pp. 4709-4718; Kishimoto, K.N., Watanabe, Y., Nakamura, H., Ectopic boneformation by electroporatic transfer of bone morphogenetic protein-4 gene (2002) Bone, 31, pp. 340-347; Sheyn, D., Kimelman-Bleich, N., Pelled, G., Ultrasound-basednonviral gene delivery induces bone formation in vivo (2008) Gene Ther, 15, pp. 257-266; Hosseinkhani, H., Inatsugu, Y., Hiraoka, Y., Impregnation of plasmid DNA into three-dimensional scaffolds and medium perfusionenhance in vitro DNA expression of mesenchymal stem cells (2005) Tissue Eng, 11, pp. 1459-1475; Hosseinkhani, H., Hosseinkhani, M., Gabrielson, N.P., DNAnanoparticles encapsulated in 3D tissue-engineered scaffolds enhanceosteogenic differentiation of mesenchymal stem cells (2007) JBiomed Mater Res A, 85, pp. 47-60; Huang, Y.C., Kaigler, D., Rice, K.G., Combined angiogenic and osteogenic factor delivery enhances bone marrow stromal celldrivenbone regeneration (2005) J Bone Miner Res, 20, pp. 848-857; Blum, J.S., Barry, M.A., Mikos, A.G., In vivo evaluation of genetherapy vectors in ex vivo-derived marrow stromal cells for boneregeneration in a rat critical-size calvarial defect model (2003) Hum GeneTher, 14, pp. 1689-1701; Aslan, H., Zilberman, Y., Arbeli, V., Nucleofection-based ex vivononviral gene delivery to human stem cells as a platform for tissueregeneration (2006) Tissue Eng, 12, pp. 877-889; Noel, D., Gazit, D., Bouquet, C., Short-term BMP-2 expression issufficient for in vivo osteochondral differentiation of mesenchymalstem cells (2004) Stem Cells, 22, pp. 74-85
Keywords: Animals; article; artificial chromosome; Bone and Bones; Bone Regeneration; bone tissue; Bone tissue engineering; cell based gene therapy; dendrimer; ex vivo gene transfer; Gene delivery; gene targeting; Gene therapy; Gene Transfer Techniques; gene vector; genetic transfection; human; Humans; in vivo gene transfer; liposome; Mesenchymal stem cell; Mesenchymal Stem Cells; nanomedicine; nanoparticle; Non-viral vectors; nonhuman; nonviral gene delivery system; polymer; protein expression; Regeneration; Regenerative Medicine; Tissue engineering; Tissue regeneration

Novel TiN x-based biosignal electrodes for electroencephalography - Fiedler, P.; Cunha, L.T.; Pedrosa, P.; Brodkorb, S.; Fonseca, C.; Vaz, F.; Haueisen, J. (Measurement Science and TechnologyMeas. Sci. Technol., 2011)
A composition, structural, morphological and electrochemical study of two titanium nitride (TiN x) thin films, sample A and sample B, obtained by dc reactive sputtering on titanium substrates was carried out in this paper. In order to assess their applicability to be used as dry electrodes, several EEG signal acquisition tests were performed using the TiN x electrodes and compared to signals acquired with conventional silver/silver-chloride (Ag/AgCl) electrodes. The two films displayed some compositional differences, as sample B was over-stoichiometric (x = 1.34, x = N/Ti atomic ratio) and sample A was close-stoichiometric (x = 0.94). XRD diffractograms showed that both samples developed a similar fcc crystalline structure (δ-TiN phase). XRD peak fitting showed that sample B (over-stoichiometric) has a more oriented structure (highly [1 1 1] textured), with larger grains. A columnar-type structure with pyramid-like shape at column's top was common to both TiN x films. This morphology, in addition to some columnar disaggregation, gives rise to a rather rough surface and porous structure. Electrochemical impedance spectroscopy results in artificial sweat showed that the electric properties of the samples remain unchanged, even after prolonged contact with sweat. The comparison of EEG signals, simultaneously recorded using the novel TiN x electrodes and conventional Ag/AgCl electrodes, showed very similar results. The root mean square deviation, which was computed for different electrode-electrolyte combinations and signal sequences of 5 s, was in the range of 4.5-9.4 νV and 6.7-20.4 νV for samples A and B, respectively. An additional test with two sets of Ag/AgCl electrodes revealed similar results, thus indicating most of the signal differences are related to the spatial distance of the compared electrodes as well as environmental noise. Therefore, our results lead to the conclusion that the novel TiN x electrodes show promising signal quality for application in EEG biosignal measurements. © 2011 IOP Publishing Ltd.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 124007CODEN: MSTCEdoi: 10.1088/0957-0233/22/12/124007Language of Original Document: EnglishCorrespondence Address: Fiedler, P.; Institute of Biomedical Engineering and Informatics, Ilmenau University of Technology, Gustav-Kirchhoff-Str. 2, 98693 Ilmenau, Germany; email: patrique.fiedler@tu-ilmenau.deReferences: Teplan, M., Fundamentals of EEG measurement (2002) Meas. Sci. Rev., 2, p. 2. , 1-11;Fonseca, C., Silva Cunha, J.P., Martins, R.E., Ferreira, V.M., Marques De Sa, J.P., Barbosa, M.A., Martins Da Silva, A., A novel dry active electrode for EEG recording (2007) IEEE Transactions on Biomedical Engineering, 54 (1), pp. 162-165. , DOI 10.1109/TBME.2006.884649, 23; Cunha, L.T., Pedrosa, P., Tavares, C.J., Alves, E., Vaz, F., Fonseca, C., The role of composition, morphology and crystalline structure in the electrochemical behaviour of TiN x thin films for dry electrode sensor materials (2009) Electrochim. Acta, 55 (1), pp. 59-67; Dias, N.S., Carmo, A., Ferreira Da Silva, A., Mendes, P.M., Correia, J.H., New dry electrodes based on iridium oxide (IrO) for non-invasive biopotential recordings and stimulation (2010) Sensors Actuators, 164 (1-2), pp. 28-34; Green, R.A., Baek, S., Poole-Warren, L.A., Martens, P.J., Conducting polymer-hydrogels for medical electrode applications (2010) Sci. Technol. Adv. Mater., 11 (1), p. 014107; Harland, C.J., Clark, T.D., Prance, R.J., Remote detection of human electroencephalograms using ultrahigh input impedance electric potential sensors (2002) Appl. Phys. Lett., 81 (17), pp. 3284-3286; Von, E.N., Spinelli, E., Muravchik, C.H., Capacitive electrodes in electroencephalography (2006) Conf. Proc. IEEE Eng. Med. Biol. Soc., 1, pp. 1126-1129; Kingsley, S.A., Sriram, S., Pollick, A., Marsh, J., Photrode optical sensor for electrophysiological monitoring (2003) Aviat. Space Environ. Med., 74, pp. 1215-1216; Fernandes, M.S., Dias, N.S., Silva, A.F., Nunes, J.S., Lanceros-Mendez, S., Correia, J.H., Mendes, P.M., Hydrogel-based photonic sensor for a biopotential wearable recording system (2010) Biosens. Bioelectron., 26 (1), pp. 80-86; Searle, A., Kirkup, L., A direct comparison of wet, dry and insulating bioelectric recording electrodes (2000) Physiological Measurement, 21 (2), pp. 271-283. , DOI 10.1088/0967-3334/21/2/307, PII S0967333400090511; Merletti, R., The electrode-skin interface and optimal detection of bioelectric signals (2010) Physiol. Meas., 31; Piscanec, S., Ciacchi, L.C., Vesselli, E., Comelli, G., Sbaizero, O., Meriani, S., De Vita, A., Bioactivity of TiN-coated titanium implants (2004) Acta Mater., 52 (5), pp. 1237-1245; Vaz, F., Ferreira, J., Ribeiro, E., Rebouta, L., Lanceros-Mendez, S., Mendes, J.A., Alves, E., De Rijk, J., Influence of nitrogen content on the structural, mechanical and electrical properties of TiN thin films (2005) Surface and Coatings Technology, 191 (2-3), pp. 317-323. , DOI 10.1016/j.surfcoat.2004.01.033, PII S025789720400060X; Vaz, F., Machado, P., Rebouta, L., Cerqueira, P., Goudeau, Ph., Riviere, J.P., Alves, E., De Rijk, J., Mechanical characterization of reactively magnetron-sputtered TiN films (2003) Surface and Coatings Technology, 174-175, pp. 375-382. , DOI 10.1016/S0257-8972(03)00711-4; Klem, G.H., Lüders, H.O., Jasper, H.H., Elger, C., The ten-twenty electrode system of the International Federation. The International Federation of Clinical Neurophysiology (1999) Electroencephalogr. Clin. Neurophysiol. Suppl., 52, pp. 3-6; Huigen, E., Peper, A., Grimbergen, C.A., Investigation into the origin of the noise of surface electrodes (2002) Med. Biol. Eng. Comput., 40 (3), pp. 332-338; Scheer, H.J., Sander, T., Trahms, L., The influence of amplifier, interface and biological noise on signal quality in high-resolution EEG recordings (2006) Physiological Measurement, 27 (2), pp. 109-117. , DOI 10.1088/0967-3334/27/2/002, PII S0967333406050039; Mayorga Martinez, C.C., Madrid, R.E., Felice, C.J., Electrochemical and geometrical characterization of iridium oxide electrodes in stainless steel substrate (2008) Sensors Actuators, 133 (2), pp. 682-686; Haueisen, J., Leistritz, L., Susse, T., Curio, G., Witte, H., Identifying mutual information transfer in the brain with differential-algebraic modeling: Evidence for fast oscillatory coupling between cortical somatosensory areas 3b and 1 (2007) Neuroimage, 37 (1), pp. 130-135; Graichen, U., Witte, H., Haueisen, J., Analysis of induced components in electroencephalograms using a multiple correlation method (2009) Biomed. Eng. Online, 8
Keywords: bioelectric; biomedical electrodes; Chlorine compounds; dc magnetron sputtering; Electric properties; Electrochemical impedance spectroscopy; Electrochemical properties; Electrodes; electroencephalography; Electrophysiology; Signal processing; signals; Surface structure; Thin films; Tinning; Titanium; Titanium nitride; titanium nitride thin films

Novel Ti/TiN dry electrodes and Ag/AgCl: A direct comparison in multichannel EEG - Fiedler, P.; Griebel, S.; Fonseca, C.; Vaz, F.; Zentner, L.; Zanow, F.; Haueisen, J. (IFMBE ProceedingsIFMBE Proc., 2011)
With up to 256 silver/silver-chloride (Ag/AgCl) electrodes, research using multichannel electroencephalography (EEG) is nowadays characterized by an increasing number of electrodes. Hence, the preparation gets more and more time-consuming and error-prone. We propose a novel electrode concept based on titanium/titanium nitride (Ti/TiN) electrodes integrated into a novel EEG cap based on fluidicdriven mechanisms. We describe the construction of our electrodes and perform EEG measurements in order to evaluate them in a multichannel setup. Therefore an additional set of conventional Ag/AgCl electrodes was integrated into the Ti/TiN EEG cap, enabling simultaneous recordings with both types of electrodes. In our tests, which included spontaneous EEG like resting state EEG, eye movements, alpha activity, and pattern reversal VEP, we found no considerable differences between compared adjacent electrodes. For the pattern reversal VEP, we found similar potential maps with both types of electrodes. In conclusion, our novel Ti/TiN electrodes have the potential to replace the conventional Ag/AgCl electrodes. © 2011 Springer-Verlag Berlin Heidelberg.
Keywords: Ag/AgCl; Alpha activities; Biomedical Electrode; biomedical electrodes; Chlorine compounds; Concept-based; Dry electrode; EEG Cap; Electric Potential; Electrodes; electroencephalography; Electrophysiology; Error prones; Eye movements; Multi-channel; Multichannel EEG; Nitrides; Potential map; Resting state; Silicone Fluidic- Driven Mechanism; Silicones; Simultaneous recording

Observer reliability and agreement: Differences, difficulties, and controversies - Costa Santos, C.; Bernardes, J.; Ayres-de-Campos, D. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Keywords: consensus; correlation coefficient; letter; methodology; organization; priority journal; reliability; research; scientific literature; validity

Pectin-based injectable biomaterials for bone tissue engineering - Munarin, F.; Guerreiro, S.G.; Grellier, M.A.; Tanzi, M.C.; Barbosa, M.A.; Petrini, P.; Granja, P.L. (BiomacromoleculesBiomacromolecules, 2011)
A variety of natural polymers and proteins are considered to be 3D cell culture structures able to mimic the extracellular matrix (ECM) to promote bone tissue regeneration. Pectin, a natural polysaccharide extracted from the plant cell walls and having a chemical structure similar to alginate, provides interesting properties as artificial ECM. In this work, for the first time, pectin, modified with an RGD-containing oligopeptide or not, is used as an ECM alternative to immobilize cells for bone tissue regeneration. The viability, metabolic activity, morphology, and osteogenic differentiation of immobilized MC3T3-E1 preosteoblats demonstrate the potential of this polysaccharide to keep immobilized cells viable and differentiating. Preosteoblasts immobilized in both types of pectin microspheres maintained a constant viability up to 29 days and were able to differentiate. The grafting of the RGD peptide on pectin backbone induced improved cell adhesion and proliferation within the microspheres. Furthermore, not only did cells grow inside but also theywere able to spread out from themicrospheres and to organize themselves in 3D structures producing a mineralized extracellular matrix. These promising results suggest that pectin can be proposed as an injectable cell vehicle for bone tissue regeneration. © 2011 American Chemical Society.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm101110xPubMed ID: 21302960Language of Original Document: EnglishCorrespondence Address: Munarin, F.; Biomatlab, Bioengineering Department, Politecnico di Milano, Piazza Leonardo da Vinci 32, 20133, Milan, Italy; email: fabiola.munarin@mail.polimi.itChemicals/CAS: arginylglycylaspartic acid, 99896-85-2; osteocalcin, 136461-80-8; pectin, 9000-69-5; Biocompatible Materials; Oligopeptides; Pectins; arginyl-glycyl-aspartic acid, 99896-85-2; pectin, 9000-69-5References: Brown, M.J., Lester, J.N., (1980) Appl. Environ. Microbiol., 40, pp. 179-185;Knox, J.P., (2008) Curr. Opin. Plant Biol., 1, pp. 308-313; Jarvis, M.C., (1984) Plant, Cell Environ, 7, pp. 153-164; Thom, D., Grant, G.T., Morris, E.R., Rees, D.A., (1982) Carbohydr. Res., 100, pp. 29-42; Fang, Y., Al-Assaf, S., Phillips, G.O., Nishinari, K., Funami, T., Williams, P.A., (2008) Carbohydr. Polym., 72, pp. 334-341; Rowley, J.A., Madlambayan, G., Mooney, D.J., (1999) Biomaterials, 20, pp. 45-53; Price, L.S., (1997) Bioessays, 19, pp. 941-943; Dee, K.C., Andersen, T.T., Bizios, R., (1999) Biomaterials, 20, pp. 221-227; Pierschbacher, M.D., Ruoslahti, E., (1984) Nature, 309, pp. 30-33; Ruoslahti, E., Pierschbacher, M., (1987) Science, 238, pp. 491-497; Hynes, R.O., (1992) Cell, 69, pp. 11-25; Yamada, K.M., (1997) Matrix Biol., 16, pp. 137-141; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H., Barrias, C.C., Salema, R., Granja, P.L., (2007) Biomaterials, 28, pp. 3644-3655; Grellier, M., Granja, P.L., Fricain, J., Bidarra, S.J., Renard, M., Bareille, R., Bourget, C., Barbosa, M.A., (2009) Biomaterials, 30, pp. 3271-3278; Liu, L., Fishman, M.L., Kost, J., Hicks, K.B., (2003) Biomaterials, 24, pp. 3333-3343; Rao, K.P., Prabhashankar, B., Kumar, A., Khan, A., Biradar, S.S., Srishail, S.P., Satyanath, B., (2003) Yale J. Biol. Med., 76, pp. 149-154; Jackson, C.L., Dreaden, T.M., Theobald, L.K., Tran, N.M., Beal, T.L., Eid, M., Gao, M.Y., Mohnen, D., (2007) Glycobiology, 17, pp. 805-819; Glinsky, V.V., Raz, A., (2009) Carbohydr. Res., 344, pp. 1788-1791; Vayssade, M., Sengkhamparn, N., Verhoef, R., Delaigue, C., Goundiam, O., Vigneron, P., Voragen, A.G., Nagel, M.D., (2010) Phytother. Res., 24, pp. 982-989; Katav, T., Liu, L., Traitel, T., Goldbart, R., Wolfson, M., Kost, J., (2008) J. Controlled Release, 130, pp. 183-191; Opanasopit, P., Apirakaramwong, A., Ngawhirunpat, T., Rojanarata, T., Ruktanonchai, U., (2008) AAPS PharmSciTech, 9, pp. 67-74; Morra, M., Cassinelli, C., Cascardo, G., Nagel, M., Della Volpe, C., Siboni, S., Maniglio, D., Ulvskov, P., (2004) Biomacromolecules, 5, pp. 2094-2104; Bussy, C., Verhoef, R., Haeger, A., Morra, M., Duval, J., Vigneron, P., Bensoussan, A., Nagel, M.D., (2008) J. Biomed. Mater. Res. A, 86, pp. 597-606; Kokkonen, H.E., Ilvesaro, J.M., Morra, M., Schols, H.A., Tuukkanen, J., (2007) Biomacromolecules, 8, pp. 509-515; Munarin, F., Giuliano, L., Bozzini, S., Tanzi, M.C., Petrini, P., (2010) Mater. Sci. Eng. C, 30, pp. 491-496; Karageorgiou, V., Kaplan, D., (2005) Biomaterials, 26, pp. 5474-5491; Volkmer, E., Drosse, I., Otto, S., Stangelmayer, A., Stengele, M., Kallukalam, B.C., Mutschler, W., Schieker, M., (2008) Tissue Eng., Part A, 14, pp. 1331-1340; Anselme, K., (2000) Biomaterials, 21, pp. 667-681; Hersel, U., Dahmen, C., Kessler, H., (2003) Biomaterials, 24, pp. 4385-4415; Stains, J.P., Civitelli, R., (2005) Birth Defects Res., Part C, 75, pp. 72-80; Ichibouji, T., Miyazaki, T., Ishida, E., Ashizuka, M., Sugino, A., Ohtsuki, C., Kuramoto, K., (2008) J. Ceram. Soc. Jpn., 116, pp. 74-78
Keywords: 3-D Cell culture; 3D Structure; 3T3 Cells; Adhesion; Alginate; animal cell; Animals; arginylglycylaspartic acid; article; Biocompatible Materials; Biopolymers; Bone; Bone and Bones; Bone Regeneration; bone tissue; Bone tissue engineering; Bone tissue regeneration; carbohydrate analysis; cell adhesion; Cell culture; cell differentiation; cell growth; cell metabolism; cell proliferation; cell spreading; cell structure; cell viability; Cells; Chemical modification; Chemical structure; controlled study; Cryoelectron Microscopy; Extracellular matrices; extracellular matrix; gene expression; immobilized cell; Immobilized cells; Injectable biomaterials; Injections; MC3T3-E1; Metabolic activity; Mice; Microscopy, Electron, Scanning; microsphere; Microspheres; Mineralized extracellular matrixes; mouse; Natural polysaccharide; nonhuman; Oligopeptides; osteoblast; osteocalcin; Osteogenic differentiation; pectin; Pectins; Plant cell culture; Plant cell wall; Preosteoblasts; priority journal; RGD peptide; Three dimensional; Tissue engineering

Scientists perception of ethical issues in nanomedicine: A case study - Silva Costa, H.; Sethe, S.; Pêgo, A.P.; Olsson, I.A.S. (NanomedicineNanomedicine, 2011)
Aim: Research and development in nanomedicine has been accompanied by the consideration of ethical issues; however, little is known about how researchers working in this area perceive such issues. This case-study explores scientists attitude towards and knowledge of ethical issues. Method: Data were collected by semi-structured interviews with 22 nanomedicine practitioners and subject to content analysis. Results: We found that scientists reflect with ambiguity on the reputed novelty of nanomedicine and what the ethical issues and risks are in their work. Respondents see no necessity for a paradigm shift in ethical considerations, but view ethical issues in nanomedicine as overlapping with those of other areas of biomedical research. Most respondents discuss ethical issues they faced in scientific work with their colleagues, but expect benefit from additional information and training on ethics. Conclusion: Our findings that scientists are motivated to reflect on ethical issues in their work, can contribute to the design of new strategies, including training programs, to engage scientists in ethical discussion and stimulate their responsibility as nanomedicine practitioners. © 2011 Future Medicine Ltd.
Keywords: adult; ambiguity; article; attitude; case study; clinical article; empirical research; ethics; Female; human; Humans; information; knowledge; male; medical ethics; medical research; Middle Aged; Models, Theoretical; nanomedicine; Nanotechnology; perception; priority journal; professional practice; qualitative study; Research Personnel; responsibility; risks; scientist; scientists perception; semi structured interview; training; Young Adult

Segmentation of ultrasound images of the carotid using RANSAC and cubic splines - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2011)
A new algorithm is proposed for the semi-automatic segmentation of the near-end and the far-end adventitia boundary of the common carotid artery in ultrasound images. It uses the random sample consensus method to estimate the most significant cubic splines fitting the edge map of a longitudinal section. The consensus of the geometric model (a spline) is evaluated through a new gain function, which integrates the responses to different discriminating features of the carotid boundary: the proximity of the geometric model to any edge or to valley shaped edges; the consistency between the orientation of the normal to the geometric model and the intensity gradient; and the distance to a rough estimate of the lumen boundary.A set of 50 longitudinal B-mode images of the common carotid and their manual segmentations performed by two medical experts were used to assess the performance of the method. The image set was taken from 25 different subjects, most of them having plaques of different classes (class II to class IV), sizes and shapes.The quantitative evaluation showed promising results, having detection errors similar to the ones observed in manual segmentations for 95% of the far-end boundaries and 73% of the near-end boundaries. © 2011 Elsevier Ireland Ltd.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: CMPBEdoi: 10.1016/j.cmpb.2010.04.015PubMed ID: 20554343Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, Portugal; email: rhr@isep.ipp.ptReferences: Baldassarre, D., Amato, M., Bondioli, A., Sirtori, C.R., Tremoli, E., Carotid artery intima-media thickness measured by ultrasonography in normal clinical practice correlates well with atherosclerosis risk factors (2000) Stroke, 31, pp. 2426-2430;O'Leary, D., Polak, J., Kronmal, R., Manolio, T., Burke, G.W.S., Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults (1999) N. Engl. J. Med., 340, pp. 14-22; Hodis, H., Mack, W., LaBree, L., Selzer, R., Liu, C., Liu, C., Azen, S., The role of carotid arterial intima-media thickness in predicting clinical coronary events (1998) Ann. Intern. Med., 128 (4), pp. 262-269; Reneman, R.S., Meinders, J.M., Hoeks, A.P.G., Non-invasive ultrasound in arterial wall dynamics in humans: what have we learned and what remains to be solved (2005) Eur. Heart J., 26, pp. 960-966; Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24 (4-5), pp. 757-777; Sonka, M., Liang, W., Stefancik, R., Stolpen, A., (2000), 2. , Handbook of Medical Imaging: Medical Image Processing and Analysis,SPIEGiannoglou, G.D., Chatzizisis, Y.S., Koutkias, V., Kompatsiaris, I., Papadogiorgaki, M., Mezaris, V., Parissi, E., Louridas, G.E., A novel active contour model for fully automated segmentation of intravascular ultrasound images: in vivo validation in human coronary arteries (2008) Comput. Biol. Med., 37 (9), pp. 1292-1302; Tsai, A., Yezzi, A.J., Tempany, C., Tucker, D., Fan, A., Grimson, W.E.L., Willsky, A.S., A shape-based approach to the segmentation of medical imagery using level sets (2003) IEEE Trans. Med. Imaging, 22 (2), pp. 137-154; Cremers, D., Kohlberger, T., Schnorr, C., Nonlinear shape statistics in Mumford-Shah based segmentation (2002) Proc. European Conf. on Computer Vision (ECCV'2002), vol. 2351, pp. 93-108; Cremers, D., Sochen, N., Schnorr, C., Towards recognition-based variational segmentation using shape priors and dynamic labeling (2003) Proc. European Conf. on Computer Vision (ECCV'2003), vol. 2695, pp. 388-400; Cremers, D., Osher, S., Soatto, S., Kernel density estimation and intrinsic alignment for knowledge-driven segmentation: teaching level sets to walk (2004) Pattern Recognit., 3175, pp. 36-44; Halenka, M., Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography (1999) Acta-Universitatis Palackianae Olomucensis Facultatis Medicae, 142, pp. 7-12; Touboul, P.J., Prati, P., Scarabin, P.-Y., Adrai, V., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertension, 10 (5), pp. 37-41; Gariepy, J., Massonneau, M., Levenson, J., Heudes, D., Simon, A., Evidence for in vivo carotid and femoral wall thickness in human hypertension (1993) J. Hypertension, 22 (1), pp. 111-118. , the Groupe de Prevention Cardio-vasculaire en Medecine du Travail; Selzer, R.H., Hodis, H.N., Kwong-Fu, H., Mack, W.J., Lee, P.L., Liu, C.R., Liu, C.H., Evaluation of computerized edge tracking for quantifying intima-media thickness of the common carotid artery from B-mode ultrasound images (1994) Atherosclerosis, 111, pp. 1-11; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Comput. Cardiol., pp. 297-300; Kozick, R.J., Detecting interfaces on ultrasound images of the carotid artery by dynamic programming (1996) SPIE, 2666, pp. 233-241; Gustavsson, T., Abu-Gharbieh, R., Hamarneh, G., Liang, Q., Implementation and comparison of four different boundary detection algorithms for quantitative ultrasonic measurements of the human carotid artery (1997) Comput. Cardiol., pp. 69-72; Detmer, P., Bashein, G., Martin, R., Matched filter identification of left-ventricle endocardial borders in transesophageal echocardiograms (1990) IEEE Trans. Med. Imaging, 9 (4), pp. 396-404; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imaging, 19 (2), pp. 127-142; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clin. Physiol., 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Sandrock, M., Pu, Q., Burkhardt, H., (1999), pp. 452-457. , Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound B-mode images using snakes, in: Int. Conf. on Image Analysis and Processing, B. WernerCheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Comput. Methods Programs Biomed., 67, pp. 27-37; Kass, M., Witkin, A., Terzopoulos, D., Snakes: active contour models (1988) Int. J. Comput. Vis., pp. 321-331; Christodoulou, C.I., Pattichis, C.S., Pantziaris, M., Nicolaides, A., Texture based classification of atherosclerotic carotid plaques (2003) IEEE Trans. Med. Imaging, 22 (7), pp. 902-912; Barratt, D., Ariff, B., Humphries, K., Thom, S., Hughes, A., Reconstruction and quantification of the carotid artery bifurcation from 3-D ultrasound images (2004) IEEE Trans. Med. Imaging, 23 (5), pp. 567-583; Fischler, M.A., Bolles, R.C., Random sample consensus: a paradigm for model fitting with applications to image analysis and automated cartography (1981) Commun. ACM, 24 (6), pp. 381-395; Rossi, A.C., Brands, P.J., Hoeks, A.P.G., Automatic recognition of the common carotid artery in longitudinal ultrasound B-mode scans (2008) Med. Image Anal., 12, pp. 653-665; Zack, G.W., Rogers, W.E., Latt, S.A., Automatic measurement of sister chromatid exchange frequency (1977) J. Histochem. Cytochem., 25 (7), pp. 741-753; Tauber, C., (2005), Filtrage anisotrope robuste et segmentation par b-spline snake: application aux images échographiques, Ph.D. thesis, Institut National Polytechnique de Toulouse, ToulouseYu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Process., 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Process., 13 (12), pp. 1640-1655; Black, M.J., Sapiro, G., Marimont, D.H., Heeger, D., Robust anisotropic diffusion (1998) IEEE Trans. Image Process., 7 (3), pp. 421-432; Rudin, L., Osher, S., Fatemi, E., Nonlinear total variation based noise removal algorithms (1992) Proceedings of the 11th Annual Int. Conf. of the Center for Nonlinear Studies on Experimental Mathematics: Computational Issues in Nonlinear Science, pp. 259-268; Rudin, L., Osher, S., Total variation based image restoration with free local constraints (1994) Proceedings of IEEE Int. Conf. on Image Processing (ICIP'94), vol. 1, pp. 31-35; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Anal. Mach. Intell., 8 (6), pp. 679-698; Guo, Z., Hall, R.W., Parallel thinning with two-subiteration algorithms (1989) Commun. ACM, 32 (3), pp. 359-373; Burden, R., Faires, J.D., (2000) Numerical Analysis, , Brooks Cole; Forsyth, D.A., Ponce, J., (2003) Computer Vision: A Modern Approach, , Prentice Hall; Marquina, A., Osher, S., Explicit algorithms for a new time dependent model based on level set motion for nonlinear deblurring and noise removal (2000) SIAM J. Sci. Comput., 22 (2), pp. 387-405; Chum, O., Matas, J., Kittler, J., (2003), 81, pp. 236-243. , Locally optimized RANSAC, in: Lecture Notes in Computer Science - Pattern Recognition, Springer Berlin/Heidelberg, Springer LNCSBland, J.M., Altman, D.G., Statistical methods for assessing agreement between two methods of clinical measurement (1986) Lancet, 1 (8476), pp. 307-310
Keywords: Algorithms; article; B scan; B-mode images; Carotid; carotid artery; Carotid Artery Diseases; Carotid Artery, Common; Class II; clinical article; Common carotid artery; Cubic spline; Detection error; echography; Edge map; Female; Gain function; Geometric models; Geometry; human; Humans; Image Interpretation, Computer-Assisted; image processing; Image segmentation; Image sets; Intensity gradients; Longitudinal section; male; Manual segmentation; mathematical model; Medical experts; Medical imaging; Non-linear smoothing; Pattern Recognition, Automated; quantitative analysis; Quantitative evaluation; random sample; Random sample consensus; RANSAC; Semi-automatic segmentation; Splines; Ultrasonic applications; Ultrasonics; Ultrasonography; Ultrasound image; Ultrasound images

Simulations of the NK cell immune synapse reveal that activation thresholds can be established by inhibitory receptors acting locally - Kaplan, A.; Kotzer, S.; Almeida, C.R.; Kohen, R.; Halpert, G.; Salmon-Divon, M.; Köhler, K.; Höglund, P.; Davis, D.M.; Mehr, R. (Journal of ImmunologyJ. Immunol., 2011)
NK cell activation is regulated by a balance between activating and inhibitory signals. To address the question of how these signals are spatially integrated, we created a computer simulation of activating and inhibitory NK cell immunological synapse (NKIS) assembly, implementing either a "quantity-based" inhibition model or a "distance-based" inhibition model. The simulations mimicked the observed molecule distributions in inhibitory and activating NKIS and yielded several new insights. First, the total signal is highly influenced by activating complex dissociation rates but not by adhesion and inhibitory complex dissociation rates. Second, concerted motion of receptors in clusters significantly accelerates NKIS maturation. Third, when the potential of a cis interaction between Ly49 receptors and MHC class I on murine NK cells was added to the model, the integrated signal as a function of receptor and ligand numbers was only slightly increased, at least up to the level of 50% cis-bound Ly49 receptors reached in the model. Fourth, and perhaps most importantly, the integrated signal behavior obtained when using the distance-based inhibition signal model was closer to the experimentally observed behavior, with an inhibition radius of the order 3-10 molecules. Microscopy to visualize Vav activation in NK cells on micropatterned surfaces of activating and inhibitory strips revealed that Vav is only locally activated where activating receptors are ligated within a single NK cell contact. Taken together, these data are consistent with a model in which inhibitory receptors act locally; that is, that every bound inhibitory receptor acts on activating receptors within a certain radius around it. Copyright © 2011 by The American Association of Immunologists, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JOIMAdoi: 10.4049/jimmunol.1002208PubMed ID: 21690326Language of Original Document: EnglishCorrespondence Address: Mehr, R.; Mina and Everard Goodman Faculty of Life Sciences, Bar-Ilan University, Ramat-Gan 52900, Israel; email: ramit.mehr@biu.ac.ilChemicals/CAS: Vav protein, 282122-55-8; intercellular adhesion molecule 1, 126547-89-5; H-2 Antigens; Histocompatibility Antigens Class I; Intercellular Adhesion Molecule-1, 126547-89-5; KLRK1 protein, human; Lymphocyte Function-Associated Antigen-1; MHC class I-related chain A; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; Receptors, KIRReferences: Burgess, S.J., Maasho, K., Masilamani, M., Narayanan, S., Borrego, F., Coligan, J.E., The NKG2D receptor: Immunobiology and clinical implications (2008) Immunol. Res., 40, pp. 18-34;González, S., López-Soto, A., Suarez-Alvarez, B., López-Vázquez, A., López-Larrea, C., NKG2D ligands: Key targets of the immune response (2008) Trends Immunol., 29, pp. 397-403; Vyas, Y.M., Maniar, H., Dupont, B., Cutting edge: Differential segregation of the Src homology 2-containing protein tyrosine phosphatase-1 within the early NK cell immune synapse distinguishes noncytolytic from cytolytic interactions (2002) Journal of Immunology, 168 (7), pp. 3150-3154; Long, E.O., Negative signaling by inhibitory receptors: The NK cell paradigm (2008) Immunol. Rev., 224, pp. 70-84; Ljunggren, H.G., Kärre, K., In search of the 'missing self': MHC molecules and NK cell recognition (1990) Immunol. Today, 11, pp. 237-244; Kane, K.P., Silver, E.T., Hazes, B., Specificity and function of activating Ly-49 receptors (2001) Immunol. Rev., 181, pp. 104-114; Lanier, L.L., Up on the tightrope: Natural killer cell activation and inhibition (2008) Nat. Immunol., 9, pp. 495-502; Radaev, S., Sun, P.D., Structure and function of natural killer cell surface receptors (2003) Annu. Rev. Biophys. Biomol. Struct., 32, pp. 93-114; Vivier, E., Nunes, J.A., Vely, F., Natural killer cell signaling pathways (2004) Science, 306 (5701), pp. 1517-1519. , DOI 10.1126/science.1103478; Yokoyama, W.M., Plougastel, B.F., Immune functions encoded by the natural killer gene complex (2003) Nat. Rev. Immunol., 3, pp. 304-316; Stebbins, C.C., Watzl, C., Billadeau, D.D., Leibson, P.J., Burshtyn, D.N., Long, E.O., Vav1 dephosphorylation by the tyrosine phosphatase SHP-1 as amechanism for inhibition of cellular cytotoxicity (2003) Mol. Cell. Biol., 23, pp. 6291-6299; Bryceson, Y.T., Long, E.O., Line of attack: NK cell specificity and integration of signals (2008) Curr. Opin. Immunol., 20, pp. 344-352; McCann, F.E., Suhling, K., Carlin, L.M., Eleme, K., Taner, S.B., Yanagi, K., Vanherberghen, B., Davis, D.M., Imaging immune surveillance by T cells and NK cells (2002) Immunol. Rev., 189, pp. 179-192; Davis, D.M., Assembly of the immunological synapse for T cells and NK cells (2002) Trends in Immunology, 23 (7), pp. 356-363. , DOI 10.1016/S1471-4906(02)02243-3, PII S1471490602022433; Vyas, Y.M., Mehta, K.M., Morgan, M., Maniar, H., Butros, L., Jung, S., Burkhardt, J.K., Dupont, B., Spatial organization of signal transduction molecules in the NK cell immune synapses during MHC class I-regulated noncytolytic and cytolytic interactions (2001) Journal of Immunology, 167 (8), pp. 4358-4367; Vyas, Y.M., Maniar, H., Lyddane, C.E., Sadelain, M., Dupont, B., Ligand binding to inhibitory killer cell Ig-like receptors induce colocalization with Src homology domain 2-containing protein tyrosine phosphatase 1 and interruption of ongoing activation signals (2004) Journal of Immunology, 173 (3), pp. 1571-1578; Orange, J.S., Formation and function of the lytic NK-cell immunological synapse (2008) Nat. Rev. Immunol., 8, pp. 713-725; Eleme, K., Taner, S.B., Onfelt, B., Collinson, L.M., McCann, F.E., Chalupny, N.J., Cosman, D., Davis, D.M., Cell surface organization of stress-inducible proteins ULBP and MICA that stimulate human NK cells and T cells via NKG2D (2004) J. Exp. Med., 199, pp. 1005-1010; Cebo, C., Da, R.S., Wittnebel, S., Turhan, A.G., Abdelali, J., Caillat-Zucman, S., Bourhis, J.H., Caignard, A., The decreased susceptibility of Bcr/Abl targets to NK cell-mediated lysis in response to imatinib mesylate involves modulation of NKG2D ligands, GM1 expression, and synapse formation (2006) Journal of Immunology, 176 (2), pp. 864-872; Burack, W.R., Lee, K.H., Holdorf, A.D., Dustin, M.L., Shaw, A.S., Cutting edge: Quantitative imaging of raft accumulation in the immunological synapse (2002) J. Immunol., 169, pp. 2837-2841; Harder, T., Engelhardt, K.R., Membrane domains in lymphocytes - From lipid rafts to protein scaffolds (2004) Traffic, 5, pp. 265-275; Laude, A.J., Prior, I.A., Plasma membrane microdomains: Organization, function and trafficking (2004) Mol. Membr. Biol., 21, pp. 193-205; Lou, Z., Jevremovic, D., Billadeau, D.D., Leibson, P.J., A balance between positive and negative signals in cytotoxic lymphocytes regulates the polarization of lipid rafts during the development of cell-mediated killing (2000) J. Exp. Med., 191, pp. 347-354; Pike, L.J., Lipid rafts: Bringing order to chaos (2003) Journal of Lipid Research, 44 (4), pp. 655-667. , DOI 10.1194/jlr.R200021-JLR200; Pizzo, P., Viola, A., Lymphocyte lipid rafts: Structure and function (2003) Curr. Opin. Immunol., 15, pp. 255-260; Rodgers, W., Farris, D., Mishra, S., Merging complexes: Properties of membrane raft assembly during lymphocyte signaling (2005) Trends Immunol., 26, pp. 97-103; Schmitz, G., Grandl, M., Update on lipid membrane microdomains (2008) Curr. Opin. Clin. Nutr. Metab. Care, 11, pp. 106-112; Wright, M.D., Moseley, G.W., Van Spriel, A.B., Tetraspanin microdomains in immune cell signalling and malignant disease (2004) Tissue Antigens, 64 (5), pp. 533-542. , DOI 10.1111/j.1399-0039.2004.00321.x; Vogt, A.B., Spindeldreher, S., Kropshofer, H., Clustering of MHCpeptide complexes prior to their engagement in the immunological synapse: Lipid raft and tetraspan microdomains (2002) Immunol. Rev., 189, pp. 136-151; Lee, S.J.E., Hori, Y., Groves, J.T., Dustin, M.L., Chakraborty, A.K., Correlation of a dynamic model for immunological synapse formation with effector functions: Two pathways to synapse formation (2002) Trends Immunol., 23, pp. 492-499; Giagulli, C., Scarpini, E., Ottoboni, L., Narumiya, S., Butcher, E.C., Constantin, G., Laudanna, C., RhoA and zeta PKC Control Distinct Modalities of LFA-1 Activation by Chemokines: Critical Role of LFA-1 Affinity Triggering in Lymphocyte In Vivo Homing (2004) Immunity, 20 (1), pp. 25-35. , DOI 10.1016/S1074-7613(03)00350-9; Masilamani, M., Nguyen, C., Kabat, J., Borrego, F., Coligan, J.E., CD94/NKG2A inhibits NK cell activation by disrupting the actin network at the immunological synapse (2006) J. Immunol., 177, pp. 3590-3596; Weikl, T.R., Lipowsky, R., Pattern formation during T-cell adhesion (2004) Biophysical Journal, 87 (6), pp. 3665-3678. , DOI 10.1529/biophysj.104.045609; Kotzer, S., Salmon-Divon, M., Kaplan, A., Almeida, C.R., Hoglund, P., Davis, D.M., Mehr, R., Modeling the influence of molecule and cell surface micro-domain distribution on the formation of T cell immunological synapses (2007) Life Science Systems and Applications Workshop, 2007. LISA 2007. IEEE/NIH. 8-9 November, , http://ieeexplore.ieee.org/xpl/freeabs_all.jsp?arnumber=4400878, Available at; Culley, F.J., Johnson, M., Evans, J.H., Kumar, S., Crilly, R., Casasbuenas, J., Schnyder, T., Ushakov, D.S., Natural killer cell signal integration balances synapse symmetry and migration (2009) PLoS Biol., 7, pp. e1000159; Treanor, B., Lanigan, P.M.P., Kumar, S., Dunsby, C., Munro, I., Auksorius, E., Culley, F.J., Neil, M.A.A., Microclusters of inhibitory killer immunoglobulin-like receptor signaling at natural killer cell immunological synapses (2006) J. Cell Biol., 174, pp. 153-161; Back, J., Chalifour, A., Scarpellino, L., Held, W., Stable masking by H-2Dd cis ligand limits Ly49A relocalization to the site of NK cell/target cell contact (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 3978-3983; Back, J., Scarpellino, L., Held, W., Probing the interactions of NK cell receptors with ligand expressed in trans and cis (2010) MethodsMol. Biol., 612, pp. 313-323; Chalifour, A., Scarpellino, L., Back, J., Brodin, P., Devèvre, E., Gros, F., Lévy, F., Held, W., A role for cis interaction between the inhibitory Ly49A receptor and MHC class I for natural killer cell education (2009) Immunity, 30, pp. 337-347; Doucey, M.A., Scarpellino, L., Zimmer, J., Guillaume, P., Luescher, I.F., Bron, C., Held, W., Cis association of Ly49A with MHC class I restricts natural killer cell inhibition (2004) Nat. Immunol., 5, pp. 328-336; Held, W., Mariuzza, R.A., Cis interactions of immunoreceptors with MHC and non-MHC ligands (2008) Nat. Rev. Immunol., 8, pp. 269-278; Scarpellino, L., Oeschger, F., Guillaume, P., Coedert, J.D., Levy, F., Leclercq, G., Held, W., Interactions of Ly49 family receptors with MHC class I ligands in trans and cis (2007) Journal of Immunology, 178 (3), pp. 1277-1284; Saffman, P.G., Delbrück, M., Brownian motion in biological membranes (1975) Proc. Natl. Acad. Sci. USA, 72, pp. 3111-3113; Raychaudhuri, S., Chakraborty, A.K., Kardar, M., Effective membrane model of the immunological synapse (2003) Phys. Rev. Lett., 91, p. 208101; Burroughs, N.J., Wülfing, C., Differential segregation in a cell-cell contact interface: The dynamics of the immunological synapse (2002) Biophys. J., 83, pp. 1784-1796; Coombs, D., Goldstein, B., Effects of the geometry of the immunological synapse on the delivery of effector molecules (2004) Biophysical Journal, 87 (4), pp. 2215-2220. , DOI 10.1529/biophysj.104.045674; Köhler, K., Xiong, S., Brzostek, J., Mehrabi, M., Eissmann, P., Harrison, A., Cordoba, S.P., Gould, K., Matched sizes of activating and inhibitory receptor/ligand pairs are required for optimal signal integration by human natural killer cells (2010) PLoS ONE, 5, pp. e15374; Dykstra, M., Cherukuri, A., Sohn, H.W., Tzeng, S.J., Pierce, S.K., Location is everything: Lipid rafts and immune cell signaling (2003) Annu. Rev. Immunol., 21, pp. 457-481; Horejsí, V., The roles of membrane microdomains (rafts) in T cell activation (2003) Immunol. Rev., 191, pp. 148-164; Fujiwara, T., Ritchie, K., Murakoshi, H., Jacobson, K., Kusumi, A., Phospholipids undergo hop diffusion in compartmentalized cell membrane (2002) Journal of Cell Biology, 157 (6), pp. 1071-1081. , DOI 10.1083/jcb.200202050; Giurisato, E., McIntosh, D.P., Tassi, M., Gamberucci, A., Benedetti, A., T cell receptor can be recruited to a subset of plasma membrane rafts, independently of cell signaling and attendantly to raft clustering (2003) J. Biol. Chem., 278, pp. 6771-6778; Kusumi, A., Koyama-Honda, I., Suzuki, K., Molecular dynamics and interactions for creation of stimulation-induced stabilized rafts from small unstable steady-state rafts (2004) Traffic, 5 (4), pp. 213-230. , DOI 10.1111/j.1600-0854.2004.0178.x; Marwali, M.R., MacLeod, M.A., Muzia, D.N., Takei, F., Lipid rafts mediate association of LFA-1 and CD3 and formation of the immunological synapse of CTL (2004) Journal of Immunology, 173 (5), pp. 2960-2967; Montixi, C., Langlet, C., Bernard, A.M., Thimonier, J., Dubois, C., Wurbel, M.A., Chauvin, J.P., He, H.T., Engagement of T cell receptor triggers its recruitment to low-density detergent-insoluble membrane domains (1998) EMBO J., 17, pp. 5334-5348; Munro, S., Lipid rafts: Elusive or illusive? (2003) Cell, 115, pp. 377-388; Pizzo, P., Giurisato, E., Bigsten, A., Tassi, M., Tavano, R., Shaw, A., Viola, A., Physiological T cell activation starts and propagates in lipid rafts (2004) Immunol. Lett., 91, pp. 3-9; Xavier, R., Brennan, T., Li, Q., McCormack, C., Seed, B., Membrane compartmentation is required for efficient T cell activation (1998) Immunity, 8, pp. 723-732; Filipp, D., Julius, M., Lipid rafts: Resolution of the "fyn problem"? (2004) Mol. Immunol., 41, pp. 645-656; Schade, A.E., Levine, A.D., Lipid raft heterogeneity in human peripheral blood T lymphoblasts: A mechanism for regulating the initiation of TCR signal transduction (2002) J. Immunol., 168, pp. 2233-2239; Janes, P.W., Ley, S.C., Magee, A.I., Aggregation of lipid rafts accompanies signaling via the T cell antigen receptor (1999) J. Cell Biol., 147, pp. 447-461; Hiltbold, E.M., Poloso, N.J., Roche, P.A., MHC class II-peptide complexes and APC lipid rafts accumulate at the immunological synapse (2003) J. Immunol., 170, pp. 1329-1338; Wülfing, C., Tskvitaria-Fuller, I., Burroughs, N., Sjaastad, M.D., Klem, J., Schatzle, J.D., Interface accumulation of receptor/ligand couples in lymphocyte activation: Methods, mechanisms, and significance (2002) Immunol. Rev., 189, pp. 64-83; Poloso, N.J., Roche, P.A., Association of MHC class II-peptide complexes with plasma membrane lipid microdomains (2004) Curr. Opin. Immunol., 16, pp. 103-107; Anderson, H.A., Hiltbold, E.M., Roche, P.A., Concentration of MHC class II molecules in lipid rafts facilitates antigen presentation (2000) Nat. Immunol., 1, pp. 156-162; Meyer Zum Bueschenfelde, C.O., Unternaehrer, J., Mellman, I., Bottomly, K., Regulated recruitment of MHC class II and costimulatory molecules to lipid rafts in dendritic cells (2004) J. Immunol., 173, pp. 6119-6124; Szollosi, J., Horejsi, V., Bene, L., Angelisova, P., Damjanovich, S., Supramolecular Complexes of MHC Class I, MHC Class II, CD20, and Tetraspan Molecules (CD53, CD81, and CD82) at the Surface of a B Cell Line JY (1996) Journal of Immunology, 157 (7), pp. 2939-2946; Leitinger, B., Hogg, N., The involvement of lipid rafts in the regulation of integrin function (2002) Journal of Cell Science, 115 (5), pp. 963-972; Cherukuri, A., Cheng, P.C., Pierce, S.K., The role of the CD19/CD21 complex in B cell processing and presentation of complement-tagged antigens (2001) J. Immunol., 167, pp. 163-172; Sheets, E.D., Holowka, D., Baird, B., Critical role for cholesterol in Lyn-mediated tyrosine phosphorylation of FcepsilonRI and their association with detergent-resistant membranes (1999) Journal of Cell Biology, 145 (4), pp. 877-887. , DOI 10.1083/jcb.145.4.877; Jordan, S., Rodgers, W., T cell glycolipid-enriched membrane domains are constitutively assembled as membrane patches that translocate to immune synapses (2003) Journal of Immunology, 171 (1), pp. 78-87; Kaizuka, Y., Douglass, A.D., Vardhana, S., Dustin, M.L., Vale, R.D., The coreceptor CD2 uses plasma membrane microdomains to transduce signals in T cells (2009) J. Cell Biol., 185, pp. 521-534; Dustin, M.L., Membrane domains and the immunological synapse: Keeping T cells resting and ready (2002) J. Clin. Invest., 109, pp. 155-160; Almeida, C.R., Davis, D.M., Segregation of HLA-C from ICAM-1 at NK cell immune synapses is controlled by its cell surface density (2006) J. Immunol., 177, pp. 6904-6910; Delon, J., The immunological synapse (2000) Curr. Biol., 10, pp. R214; Anton Van Der Merwe, P., Davis, S.J., Shaw, A.S., Dustin, M.L., Cytoskeletal polarization and redistribution of cell-surface molecules during T cell antigen recognition (2000) Semin. Immunol., 12, pp. 5-21; Bossi, G., Trambas, C., Booth, S., Clark, R., Stinchcombe, J., Griffiths, G.M., The secretory synapse: The secrets of a serial killer (2002) Immunol. Rev., 189, pp. 152-160; Endt, J., McCann, F.E., Almeida, C.R., Urlaub, D., Leung, R., Pende, D., Davis, D.M., Watzl, C., Inhibitory receptor signals suppress ligation-induced recruitment of NKG2D to GM1-rich membrane domains at the human NK cell immune synapse (2007) Journal of Immunology, 178 (9), pp. 5606-5611; Gasser, S., Raulet, D.H., Activation and self-tolerance of natural killer cells (2006) Immunol. Rev., 214, pp. 130-142; Rubio, G., Férez, X., Sánchez-Campillo, M., Gálvez, J., Martí, S., Verdú, R., Hernández-Caselles, T., García-Peñarrubia, P., Cross-linking of MHC class I molecules on human NK cells inhibits NK cell function, segregates MHC I from the NK cell synapse, and induces intracellular phosphotyrosines (2004) J. Leukoc. Biol., 76, pp. 116-124; Kaizuka, Y., Douglass, A.D., Varma, R., Dustin, M.L., Vale, R.D., Mechanisms for segregating T cell receptor and adhesion molecules during immunological synapse formation in Jurkat T cells (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 20296-20301; Brodin, P., Lakshmikanth, T., Mehr, R., Johansson, M.H., Duru, A.D., Achour, A., Salmon-Divon, M., Johansson, S., Natural killer cell tolerance persists despite significant reduction of self MHC class I on normal target cells in mice (2010) PLoS ONE, 5, pp. e1317; Carlin, L.M., Eleme, K., McCann, F.E., Davis, D.M., Intercellular transfer and supramolecular organization of human leukocyte antigen C at inhibitory natural killer cell immune synapses (2001) J. Exp. Med., 194, pp. 1507-1517; Fassett, M.S., Davis, D.M., Valter, M.M., Cohen, G.B., Strominger, J.L., Signaling at the inhibitory natural killer cell immune synapse regulates lipid raft polarization but not class I MHC clustering (2001) Proc. Natl. Acad. Sci. USA, 98, pp. 14547-14552; Faure, M., Barber, D.F., Takahashi, S.M., Jin, T., Long, E.O., Spontaneous clustering and tyrosine phosphorylation of NK cell inhibitory receptor induced by ligand binding (2003) J. Immunol., 170, pp. 6107-6114; Standeven, L.J., Carlin, L.M., Borszcz, P., Davis, D.M., Burshtyn, D.N., The actin cytoskeleton controls the efficiency of killer Ig-like receptor accumulation at inhibitory NK cell immune synapses (2004) J. Immunol., 173, pp. 5617-5625; Abeyweera, T.P., Merino, E., Huse, M., Inhibitory signaling blocks activating receptor clustering and induces cytoskeletal retraction in natural killer cells (2011) J. Cell Biol., 192, pp. 675-690; Labadia, M.E., Jeanfavre, D.D., Caviness, G.O., Morelock, M.M., Molecular regulation of the interaction between leukocyte function-associated antigen-1 and soluble ICAM-1 by divalent metal cations (1998) J. Immunol., 161, pp. 836-842; Tominaga, Y., Kita, Y., Satoh, A., Asai, S., Kato, K., Ishikawa, K., Horiuchi, T., Takashi, T., Affinity and kinetic analysis of the molecular interaction of ICAM-1 and leukocyte function-associated antigen-1 (1998) Journal of Immunology, 161 (8), pp. 4016-4022; Maenaka, K., Van Der Merwe, P.A., Stuart, D.I., Jones, E.Y., Sondermann, P., The human low affinity Fcgamma receptors IIa, IIb, and III bind IgG with fast kinetics and distinct thermodynamic properties (2001) J. Biol. Chem., 276, pp. 44898-44904; Dustin, M.L., Ferguson, L.M., Chan, P.Y., Springer, T.A., Golan, D.E., Visualization of CD2 interaction with LFA-3 and determination of the twodimensional dissociation constant for adhesion receptors in a contact area (1996) J. Cell Biol., 132, pp. 465-474; Sloan-Lancaster, J., Presley, J., Ellenberg, J., Yamazaki, T., Lippincott-Schwartz, J., Samelson, L.E., ZAP-70 association with T cell receptor zeta (TCRzeta): Fluorescence imaging of dynamic changes upon cellular stimulation (1998) J. Cell Biol., 143, pp. 613-624; Von Essen, M., Bonefeld, C.M., Siersma, V., Rasmussen, A.B., Lauritsen, J.P.H., Nielsen, B.L., Geisler, C., Constitutive and ligand-induced TCR degradation (2004) Journal of Immunology, 173 (1), pp. 384-393; Groves, J.T., Wulfing, C., Boxer, S.G., Electrical manipulation of glycan-phosphatidyl inositol-tethered proteins in planar supported bilayers (1996) Biophys. J., 71, pp. 2716-2723; Krogsgaard, M., Li, Q.J., Sumen, C., Huppa, J.B., Huse, M., Davis, M.M., Agonist/endogenous peptide-MHC heterodimers drive T cell activation and sensitivity (2005) Nature, 434, pp. 238-243; Dimasi, N., Sawicki, M.W., Reineck, L.A., Li, Y., Natarajan, K., Margulies, D.H., Mariuzza, R.A., Crystal structure of the Ly49I natural killer cell receptor reveals variability in dimerization mode within the Ly49 family (2002) J. Mol. Biol., 320, pp. 573-585; Natarajan, K., Boyd, L.F., Schuck, P., Yokoyama, W.M., Eliat, D., Margulies, D.H., Interaction of the NK cell inhibitory receptor Ly49A with H-2Dd: Identification of a site distinct from the TCR site (1999) Immunity, 11, pp. 591-601; O'Callaghan, C.A., Cerwenka, A., Willcox, B.E., Lanier, L.L., Bjorkman, P.J., Molecular competition for NKG2D: H60 and RAE1 compete unequally for NKG2D with dominance of H60 (2001) Immunity, 15, pp. 201-211; Borrego, F., Masilamani, M., Marusina, A.I., Tang, X., Coligan, J.E., The CD94/NKG2 family of receptors: From molecules and cells to clinical relevance (2006) Immunol. Res., 35, pp. 263-278
Keywords: animal cell; animal experiment; Animals; antigen recognition; article; cell maturation; cell membrane; Computer simulation; controlled study; dissociation; H-2 Antigens; Histocompatibility Antigens Class I; HLA antigen; HLA C antigen; Humans; immunological synapse; Immunological Synapses; intercellular adhesion molecule 1; Intercellular Adhesion Molecule-1; killer cell immunoglobulin like receptor 2DL1; Killer Cells, Natural; lymphocyte activation; lymphocyte function associated antigen 1; Lymphocyte Function-Associated Antigen-1; major histocompatibility antigen class 1; Membrane Microdomains; Mice; Models, Immunological; mouse; natural killer cell; natural killer cell receptor NKG2D; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; nonhuman; priority journal; protein assembly; Receptors, KIR; signal transduction; steady state; Vav protein

Systemic delivery of bone marrow-derived mesenchymal stromal cells diminishes neuropathology in a mouse model of Krabbe's disease - Miranda, C.O.; Teixeira, C.A.; Liz, M.A.; Sousa, V.F.; Franquinho, F.; Forte, G.; Di Nardo, P.; Pinto-Do-Ó, P.; Sousa, M.M. (Stem Cells, 2011)
Cited By (since 1996):4Export Date: 2 October 2013Source: Scopus

Access to computerised analysis of intrapartum cardiotocographs improves clinicians' prediction of newborn umbilical artery blood pH - Costa, A.; Santos, C.; Ayres-de-Campos, D.; Costa, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2010)
Objective To evaluate the impact of access to computerised cardiotocograph (CTG) analysis on reproducibility and accuracy of clinicians' predictions of umbilical artery blood pH (UAB pH) and 5-minute Apgar score. Design Prospective evaluation of pre-recorded cases. Setting A tertiary-care university hospital. Population From databases of intrapartum CTGs acquired in singleton term pregnancies, 204 tracings with low signal loss and short time interval to delivery were consecutively selected. Methods Tracings were randomly assigned to computer analysis by the Omniview-SisPorto 3.5 ® system (study group n = 104) or to no analysis (control group n = 100). Three experienced clinicians evaluated all tracing printouts independently and were asked to predict the newborns' UAB pH and 5-minute Apgar scores from them. Main outcome measures Interobserver agreement (measured by the intraclass correlation coefficient [ICC]) and accuracy in prediction of neonatal outcomes with 95% CI. Results Agreement on prediction of UAB pH was significantly higher in the study group (ICC = 0.70; 95% CI 0.61-0.77) than in the control group (ICC = 0.43; 95% CI 0.21-0.60), and a trend towards better agreement was also seen in estimation of 5-minute Apgar scores (ICC = 0.55; 95% CI 0.38-0.68 versus ICC = 0.43; 95% CI 0.25-0.57). Observers predicted UAB pH values correctly within a 0.10 margin in 70% of cases in the study group (95% CI 0.61-0.79) versus 46% in the control group (95% CI 0.35-0.56). They predicted 5-minute Apgar scores within a margin of one in 81% of cases in the study group (95% CI 0.73-0.88) and in 70% of cases in the control group (95% CI 0.61-0.79). Conclusions Prediction of UAB pH is more reproducible and accurate when clinicians have access to computerised analysis of CTGs. © RCOG 2010 BJOG An International Journal of Obstetrics and Gynaecology.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2010.02645.xPubMed ID: 20618316Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina da Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: cosantonia@gmail.comReferences: Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-10;Donker, D.K., Van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-8; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-65; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-5; Ayres-De-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto ® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-4; Costa, A., Ayres-De-Campos, D., Costa, F., Santos, C., Bernardes, J., Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals (2009) Am J Obstet Gynecol, 201, pp. 464e1-6. , Jun 17. [Epub ahead of print]; Westerhuis, M., Van Horen, E., Kwee, A., Van Dertweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-51; Ayres-De-Campos, D., Bernardes, J., Marsalb, K., Nickelsen, C., Makarainend, L., Banfield, P., Can the reproducibility of fetal heart rate baseline estimation be improved? (2004) Eur J Obstet Gynecol Reprod Biol, 112, pp. 49-54; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in Obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-75; Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-10. , ACOG technical bulletin; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-63; Costa-Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG, 112, pp. 667-9; Bland, J.M., Altman, D.G., Agreement between methods of measurement with multiple observations per individual (2007) J Biopharm Stat, 17, pp. 571-82; Chauhan, S.P., Klauser, C.K., Woodring, T.C., Sanderson, M., Magann, E.F., Morrison, J.C., Intrapartum nonreassuring fetal heart rate tracing and prediction of adverse outcomes: Interobserver variability (2008) Am J Obstet Gynecol, 199, pp. 623e1-e5; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464
Keywords: access to information; Apgar score; arterial pH; article; Cardiotocography; clinical competence; computer analysis; computerised analysis; controlled study; delivery; Diagnosis, Computer-Assisted; diagnostic accuracy; Female; Fetal Blood; Fetal heart rate; Fetal monitoring; Gestational Age; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; male; neonatal acidaemia; Neonatology; newborn; observer variation; outcome assessment; prediction; Pregnancy; priority journal; Prospective Studies; prospective study; reproducibility; Umbilical Arteries; umbilical artery; university hospital

Adhesion of human leukocytes on mixtures of hydroxyl- and methyl-terminated self-assembled monolayers: Effect of blood protein adsorption - Barbosa, J.N.; Martins, M.C.L.; Freitas, S.C.; Gonçalves, I.C.; Águas, A.P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
The adhesion of human leukocytes to nanostructured surfaces with different chemical properties and the effect of protein adsorption were investigated. Selfassembled monolayers (SAMs) prepared with mixtures of methyl- and hydroxyl-terminated alkanethiols in different percentages on gold were used. The surfaces were preimmersed in distinct protein solutions (human serum albumin, human fibrinogen, and autologous plasma). Adherent leukocytes were analyzed both by light and SEM. SAMs submitted to pre-immersion in plasma presented higher numbers of adherent leukocytes in the pure OH-terminated SAM, whereas methyl-terminated surfaces accounted for the lowest number of adherent cells. We observed a general increase in the number of adherent human leukocytes as the percentage of OH groups on the surface of the SAMs increased for all the pre-immersion conditions investigated. The number of adherent human leukocytes is highly influenced by the pre-immersion conditions used, and this observation is particularly relevant in the case of the methyl-terminated SAMs. The results obtained demonstrate that surface chemistry has a major influence in leukocyte adhesion to biomaterials, and that pre-immersion in protein solutions has a determinant effect in leukocyte adhesion. © 2009 Wiley Periodicals, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32480PubMed ID: 19484768Language of Original Document: EnglishCorrespondence Address: Barbosa, J. N.; Divisão de Biomateriais, INEB-Instituto de Engenharia Biomédica, Universidade do Porto, Porto 4150-180, Portugal; email: judite@ineb.up.ptChemicals/CAS: Blood Proteins; Gold, 7440-57-5; Hydroxyl Radical, 3352-57-6References: Brodbeck, W.G., Nakayama, Y., Matsuda, T., Colton, E., Ziats, N.P., Anderson, J.M., Biomaterial surface chemistry dictates adherent monocyte/macrophage cytokine expression in vitro (2002) Cytokine, 18, pp. 311-319;Kao, W.Y.J., Evaluation of leukocyte adhesion on polyurethanes: The effects of shear stress and blood proteins (2000) Biomaterials, 21, pp. 2295-2303; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Nimeri, G., Ohman, L., Elwing, H., Wettero, J., Bengtsson, T., The influence of plasma proteins and platelets on oxygen radical production and F-actin distribution in neutrophils adhering to polymer surfaces (2002) Biomaterials, 23, pp. 1785-1795; Wettero, J., Bengtsson, T., Tengvall, P., C1q-independent activation of neutrophils by immunoglobulin M-coated surfaces (2001) J Biomed Mater Res, 57, pp. 550-558; Yung, L.Y.L., Colman, R.W., Cooper, S.L., Neutrophil adhesion on polyurethanes preadsorbed with high molecular weight kininogen (1999) Blood, 94, pp. 2716-2724; Eriksson, C., Nygren, H., Polymorphonuclear leukocytes in coagulating whole blood recognize hydrophilic and hydrophobic titanium surfaces by different adhesion receptors and show different patterns of receptor expression (2001) J Lab Clin Med, 137, pp. 296-302; Tang, L.P., Eaton, J.W., Mechanism of acute inflammatory response to biomaterials (1994) Cell Mater, 4, pp. 429-436; Tang, L.P., Eaton, J.W., Inflammatory responses to biomaterials (1995) Am J Clin Pathol, 103, pp. 466-471; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (1999) J Biomed Mater Res, 49, pp. 435-447; Collier, T.O., Anderson, J.M., Protein and surface effects on monocyte and macrophage adhesion, maturation, and survival (2002) J Biomed Mater Res, 60, pp. 487-496; Yun, J.K., Defife, K., Colton, E., Stack, S., Azeez, A., Cahalan, L., Verhoeven, M., Anderson, J.M., Human monocytemacrophage adhesion and cytokine production on surface-modified poly(tetrafluoroethylene hexafluoropropylene) polymers with and without protein preadsorption (1995) J Biomed Mater Res, 29, pp. 257-268; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrksich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Mrksich, M., Model substrates for studying and controlling cell adhesion (2000) Abstr Pap Am Chem Soc, 219, pp. U572-U572; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolavers (2003) J Biomed Mater Res, 67 A, pp. 158-171. , Part A; Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110; Tang, L.P., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Bergman, A.J., Zygourakis, K., Migration of lymphocytes on fibronectin-coated surfaces: Temporal evolution of migratory parameters (1999) Biomaterials, 20, pp. 2235-2244; Taborelli, M., Eng, L., Descouts, P., Ranieri, J.P., Bellamkonda, R., Aebischer, P., Bovine serum-albumin conformation on methyl and amine functionalized surfaces compared by scanning force microscopy (1995) J Biomed Mater Res, 29, pp. 707-714; Liu, L., Elwing, H., Complement activation on thiol-modi.ed gold surfaces (1996) J Biomed Mater Res, 30, pp. 535-541; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Hirata, I., Hioko, Y., Toda, M., Kitazawa, T., Murakami, Y., Kitano, E., Kitamura, H., Iwata, H., Deposition of complement protein C3b on mixed self-assembled monolayers carrying surface hydroxyl and methyl groups studied by surface plasmon resonance (2003) J Biomed Mater Res, 66 A, pp. 669-676. , Part A; Kalltorp, M., Oblogina, S., Jacobsson, S., Karlsson, A., Tengvall, P., Thomsen, P., In vivo cell recruitment, cytokine release and chemiluminescence response at gold, and thiol functionalized surfaces (1999) Biomaterials, 20, pp. 2123-2137; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polym Ed, 4, pp. 591-599; Brash, J.L., Tenhove, P., Effect of plasma dilution on adsorption of fibrinogen to solid-surfaces (1984) Thromb Haemost, 51, pp. 326-330; Tang, L.P., Ugarova, T.P., Plow, E.F., Eaton, J.W., Molecular determinants of acute inflammatory responses to biomaterials (1996) J Clin Invest, 97, pp. 1329-1334; Thomsen, P., Gretzer, C., Macrophage interactions with modified material surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Werthen, M., Sellborn, A., Kalltorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Wettero, J., Bengtsson, T., Tengvall, P., Complement activation on immunoglobulin G-coated hydrophobic surfaces enhances the release of oxygen radicals from neutrophils through an actin-dependent mechanism (2000) J Biomed Mater Res, 51, pp. 742-751; Jenney, C.R., Anderson, J.M., Adsorbed IgG: A potent adhesive substrate for human macrophages (2000) J Biomed Mater Res, 50, pp. 281-290; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkane thiols on gold surfaces (1997) Biomaterials, 18, pp. 1059-1068; Roach, P., Farrar, D., Perry, C.C., Interpretation of protein adsorption: Surface-induced conformational changes (2005) J Am Chem Soc, 127, pp. 8168-8173; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res, 65 A, pp. 429-434. , Part A; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold (2004) Biomaterials, 25, pp. 2557-2563; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Inflammatory cell recruitment and adhesion to methyl-terminated selfassembled monolayers: Effect of implantation time (2005) Microsc Res Tech, 66, pp. 37-42; Barbosa, J.N., Madureira, P., Barbosa, M.A., Aguas, A.P., The attraction of Mac-1(+) phagocytes during acute inflammation by methyl-coated self-assembled monolayers (2005) Biomaterials, 26, pp. 3021-3027
Keywords: Adherent cells; Adhesion; Adsorption; Alkanethiols; article; Biological materials; biomaterial; Blood protein adsorption; Blood Proteins; cell adhesion; Cell Count; Chemical properties; gold; human; human cell; Human leukocytes; Human serum albumins; Humans; hydroxyl group; Hydroxyl Radical; Hydroxyl-terminated; immersion; Inflammatory response; leukocyte adherence; Leukocyte adhesion; Leukocytes; Nanostructured materials; Nanostructured surface; Nanostructured surfaces; OH group; Protein adsorption; protein blood level; Protein solution; Proteins; Sams; Scanning electron microscopy; Self assembled monolayers; Self-assembled monolayers; SEM; Surface chemistry; Surface Properties

Analysis of heart rate variability in a rat model of induced pulmonary hypertension - Gonçalves, H.; Henriques-Coelho, T.; Bernardes, J.; Rocha, A.P.; Brandão-Nogueira, A.; Leite-Moreira, A. (Medical Engineering and PhysicsMed. Eng. Phys., 2010)
Monocrotaline (MCT) is commonly used to experimentally induce pulmonary hypertension (PH), which might lead to chronic heart failure. In this study, linear and non-linear heart rate (HR) dynamics were weekly assessed in MCT-treated and non-treated Wistar rats.The HR of 10 adult Wistar rats injected with MCT (MCT group) and of 10 similar rats injected with vehicle (non-MCT group), anesthetized with Ketamine, was weekly recorded during 4 weeks. The first four segments of 1-min length of each HR recording were analysed using linear, time and frequency domains, and approximate (ApEn) and sample (SampEn) entropy indices, considering recently proposed values for the threshold parameter of ApEn and SampEn. Statistical analysis was performed using 95% confidence intervals and statistical tests.Along the study period, an overall weekly maintenance of HR indices, or a decrease, namely in weeks 1-2, was manifest, in the MCT group, except for LF and LF/HF, in week 1, denoting a short-term increase in sympathetic activity without any other changes. On the other hand, a maintenance of HR indices, or an increase, namely on week 4, was observed in the non-MCT group, except for LF/HF, denoting a long-term increase of the overall activity of HR control systems, with a parasympathetic like dominance.Studies on long-term HR dynamics should be performed in very carefully controlled experimental settings, as significant weekly changes may occur, both among anesthetized MCT-treated and non-treated rats. © 2010 IPEM.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MEPHEdoi: 10.1016/j.medengphy.2010.04.018PubMed ID: 20547091Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Geociências, Ambiente e Ordenamento do Território, Faculdade de Ciências, Universidade do Porto, Rua do Campo Alegre 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptChemicals/CAS: monocrotaline, 315-22-0, 8051-27-2; Ketamine, 6740-88-1; Monocrotaline, 315-22-0References: (2005), ACOG, American College of Obstetricians and Gynecologists. ACOG Practice Bulletin. Clinical Management Guidelines for Obstetrician-Gynecologists, Number 70, December 2005. Obstet Gynecol 106(6):1453-60Akhavein, F., St.-Michel, E.J., Seifert, E., Rohlicek, C.V., Decreased left ventricular function, myocarditis, and coronary arteriolar medial thickening following monocrotaline administration in adult rats (2007) J Appl Physiol, 103 (1), pp. 287-295;Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am J Physiol Heart Circ Physiol, 290 (6), pp. H2560-H2570; Bernardes, J., Costa-Pereira, A., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Bernardes, J., Gonçalves, H., Ayres-de-Campos, D., Rocha, A.P., Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states (2008) Early Hum Dev, 84, pp. 433-439; Bruijnzeel, A.W., Stam, R., Croiset, G., Wiegant, G.M., Long-term sensitization of cardiovascular stress responses after a single stressful experience (2001) Physiol Behav, 73 (1-2), pp. 81-86; Cerutti, C., Gustin, M.P., Paultre, C.Z., Lo, M., Julien, C., Vincent, M., Autonomic nervous-systempulmonary-edema and cardiovascular variability in rats-a spectral-analysis approach (1991) Am J Physiol, 261 (84), pp. H1292-H1299; Court, D.J., Parer, J.T., Nathanielsz, P.W., Parer, J.T., (1984) Experimental studies of fetal asphyxia and fetal heart rate interpretation Research in Perinatal Medicine, pp. 113-169. , Perinatology Press, New York; Dudewicz, E., Mishra, S., (1988) Modern mathematical statistics, , Jonh Wiley and Sons, Inc; Falcao-Pires, I., Gonçalves, N., Henriques-Coelho, T., Roncon-Albuquerque, R., Moreira-Gonçalves, D., Leite-Moreira, A.F., Administration of Apelin modulates myocardial. expression of Apelin-APJ and improves right ventricular performance in MCT-induced pulmonary hypertension (2008) Circulation, 118, pp. S285; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: the effect on linear and nonlinear parameters (2006) Physiol Meas, 27 (3), pp. 307-319; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med Biol Eng Comput, 44 (10), pp. 847-855; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum Dev, 83, pp. 585-591; Gonçalves, H., Henriques-Coelho, T., Bernardes, J., Rocha, A.P., Nogueira, A., Leite-Moreira, A., Linear and nonlinear heart rate analysis in a rat model of acute anoxia (2008) Physiol Meas, 29, pp. 1133-1143; Henriques-Coelho, T., Correia-Pinto, J., Roncon-Albuquerque, R., Baptista, M.J., Lourenco, A.P., Oliveira, S.M., Endogenous production of ghrelin and beneficial effects of its exogenous administration in monocrotaline-induced pulmonary hypertension (2004) Am J Physiol Heart Circ Physiol, 287 (6), pp. H2885-H2890; Henriques-Coelho, T., Oliveira, S.M., Moura, R.S., Roncon-Albuquerque, R., Neves, A.L., Santos, M., Thymulin inhibits monocrotaline-induced pulmonary hypertension modulating interleukin-6 expression and suppressing p38 pathway (2008) Endocrinology, 149 (9), pp. 4367-4373; Hessel, M.H.M., Steendijk, P., den Adel, B., Schutte, C.I., van der Laarse, A., Characterization of right ventricular function after monocrotaline-induced pulmonary hypertension in the intact rat (2006) Am J Physiol Heart Circ Physiol, 291 (5), pp. H2424-H2430; Kuwahara, M., Yayou, K., Ishii, K., Hashimoto, S., Tsubone, H., Sugano, S., Power spectral analysis of heart rate variability as a new method for assessing autonomic activity in the rat (1994) J Electrocardiol, 27 (4), pp. 333-337; Leineweber, K., Brandt, K., Wludyka, B., Beilfuss, A., Ponicke, K., Heinroth-Hoffmann, I., Ventricular hypertrophy plus neurohumoral activation is necessary to alter the cardiac beta-adrenoceptor system in experimental heart failure (2002) Circ Res, 91 (11), pp. 1056-1062; Lourenço, A.P., Roncon-Albuquerque, R., Bras-Silva, C., Faria, B., Wieland, J., Henriques-Coelho, T., Myocardial dysfunction and neurohumoral activation without remodeling in left ventricle of monocrotaline-induced pulmonary hypertensive rats (2006) Am J Physiol Heart Circ Physiol, 291 (4), pp. H1587-H1594; Magenes, G., Signorini, M.G., Arduini, D., Cerutti, S., Fetal heart rate variability due to vibroacoustic stimulation: linear and nonlinear contribution (2004) Methods Inf Med, 43 (1), pp. 47-51; Marshall, B.E., Longnecker, D.E., General anesthetics (1996) Goodman & Gilman's. The pharmacological basis of therapeutics, , McGraw-Hill, New York, J.G. Hardman, A.G. Gilman, L.E. Limbird (Eds.); Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press; Miller, W.C., Rice, D.L., Kreusel, R.G., Bedrossian, C.W.M., Monocrotaline model of noncardiogenic pulmonary-edema in dogs (1978) J Appl Physiol, 45 (6), pp. 962-965; Montenegro, N., Bernardes, J., Ayres-de-Campos, D., Matias, A., Areias, J.C., Monitoring of cardiac-extracardiac haemodynamics and automated fetal heart rate preceding intrauterine death (1996) Eur J Obstet Gynecol Reprod Biol, 64 (1), pp. 3-6; Moraru, L., Cimponeriu, L., Tong, S., Thakor, N., Bezerianos, A., Characterization of heart rate variability changes following asphyxia in rats (2004) Methods Inf Med, 43 (1), pp. 118-121; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin Obstet Gynaecol, 8 (3), pp. 643-661; Parati, G., Mancia, G., Di Rienzo, M., Castiglioni, P., Taylor, J.A., Studinger, P., Point: Counterpoint: Cardiovascular variability is/is not an index of autonomic control of circulation (2006) J Appl Physiol, 101 (2), pp. 676-682; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79, pp. 249-255; Pincus, S., Aproximate entropy (ApEn) as a complexity measure (1995) Chaos, 5, pp. 110-117; Pincus, S.M., Gevers, E.F., Robinson, I.C.A.F., VanDenBerg, G., Roelfsema, F., Hartman, M.L., Females secrete growth hormone with more process irregularity than males in both humans and rats (1996) Am J Physiol-Endocrinol Metab, 270 (1), pp. E107-E115; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Sanyal, S.N., Ono, K., Derangement of autonomic nerve control in rat with right ventricular failure (2002) Pathophysiology, 8 (3), pp. 197-203; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50, pp. 365-373; (1996), Task force, Heart rate variability - standards of measurement, physiological interpretation and clinical use Circulation 93 1043-65 Task force of the European Society of Cardiology and the North American Society of Pacing and ElectrophysiologyTaylor, J.A., Studinger, P., Cardiovascular variability is/is not an index of autonomic control of circulation (2006) J Appl Physiol, 101 (2), pp. 690-691; Welch, P.D., The use of Fast Fourier Transform for the estimation of power spectra: a method based on time averaging over short, modified periodograms (1967) IEEE Trans Audio Electroacous, AU-15 (2), pp. 70-73; Yum, M.K., Park, E.Y., Kim, C.R., Hwang, J.H., Alterations in irregular and fractal heart rate behavior in growth restricted fetuses (2001) Eur J Obstet Gynecol, 94, pp. 51-58
Keywords: adrenergic activity; Amines; animal experiment; animal model; Animals; article; cholinergic activity; Chronic heart failures; Confidence interval; controlled study; Disease Models, Animal; Electrocardiography; entropy; Female; Frequency domain analysis; Frequency domains; Heart; heart electrophysiology; Heart rate; Heart rate variability; Heart rate variability (HRV); Heart rates; Hypertension, Pulmonary; Injections, Subcutaneous; Ketamine; Maintenance; Monocrotaline; Non-linear; nonhuman; priority journal; Pulmonary hypertension; rat; Rat model; Rats; Rats, Wistar; Statistical analysis; statistical parameters; Sympathetic activities; Threshold parameters; Time and frequency domain analysis; Time domain analysis; Time Factors; Wistar rat; Wistar rats

Anti-adhesion and antiproliferative cellulose triacetate membrane for prevention of biomaterial-centred infections associated with Staphylococcus epidermidis - Extremina, C.I.; Fonseca, A.F.d.; Granja, P.L.; Fonseca, A.P. (International Journal of Antimicrobial AgentsInt. J. Antimicrob. Agents, 2010)
The initial step in preventing biomaterial-associated infections consists of preventing bacterial adhesion to the device surface. One possible approach is the design of antibiotic-releasing biomaterials. Cellulose triacetate (CTA) membranes with the antibiotic imipenem (IPM) entrapped (CTA-IPM) were prepared. The material was characterised in terms of surface morphology by scanning electron microscopy, surface free energy of interaction and X-ray photoelectron spectroscopy (XPS). Antibiotic release studies were also performed. In vitro adhesion of Staphylococcus epidermidis RP62A to CTA-IPM was investigated using a modified microtitre plate assay, and the antibacterial activity of the CTA-IPM membrane was assessed by a modified Kirby-Bauer test, which showed effective entrapment of the antibiotic as confirmed by XPS and hydrophilicity assays. Release studies showed that this drug-polymer conjugate serves as an adequate reservoir for sustained release of IPM over a period of 71 h at an effective bacteriostatic concentration. Moreover, bacterial adhesion tests showed a statistically significant decrease in the adhesion of S. epidermidis RP62A to CTA-IPM compared with its adhesion to CTA alone. The present innovative approach is capable of providing a membrane with anti-adhesive and antiproliferative properties, thus encouraging in vivo studies to provide a better simulation of the clinical situation. © 2009 Elsevier B.V. and the International Society of Chemotherapy.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: IAAGEdoi: 10.1016/j.ijantimicag.2009.09.017PubMed ID: 19942411Language of Original Document: EnglishCorrespondence Address: Extremina, C.I.; REQUIMTE, Faculdade de Farmácia, Universidade do Porto, Rua Aníbal Cunha 164, 4050-047 Porto, Portugal; email: extremina@gmail.comChemicals/CAS: cellulose triacetate, 9012-09-3; cilastatin plus imipenem, 92309-29-0; Anti-Bacterial Agents; Biocompatible Materials; Cellulose, 9004-34-6; Imipenem, 74431-23-5; cellulose triacetate, 9012-09-3Tradenames: tienam, Merck Sharp and Dohme, GermanyManufacturers: Eastman Kodak, Netherlands; Merck Sharp and Dohme, GermanyReferences: Darouiche, R.O., Treatment of infections associated with surgical implants (2004) N Engl J Med, 350, pp. 1422-1429;Fonseca, A.P., Extremina, C., Fonseca, A.F., Sousa, J.C., Effect of subinhibitory concentration of piperacillin/tazobactam on Pseudomonas aeruginosa (2004) J Med Microbiol, 53, pp. 903-910; Donelli, G., Francolini, I., Piozzi, A., Di Rosa, R., Marconi, W., New polymer-antibiotic systems to inhibit bacterial biofilm formation: a suitable approach to prevent central venous catheter-associated infections (2002) J Chemother, 14, pp. 501-507; Akiyama, H., Okamoto, S., Prophylaxis of indwelling urethral catheter infection: clinical experience with a modified Foley catheter and drainage system (1979) J Urol, 121, pp. 40-42; Granja, P.L., Baquey, C., Pouységu, L., Bareille, R., De Jéso, B., Barbosa, M.A., Cellulose-based biomaterials for bone regeneration: hemi-synthesis and characterisation (1996) Proceedings of polymers in medicine and surgery-PIMS'96, pp. 73-80. , Glasgow, UK; Elam, J.H., Karlsson, C.H., Nygren, H., Pre-adsorption of cellulose ether onto polymer surfaces: adsorption of adhesins and platelet activation (1992) Biomaterials, 14, pp. 233-237; Fonseca, A.P., Granja, P.L., Nogueira, J.A., Oliveira, D.R., Barbosa, M.A., Staphylococcus epidermidis RP62A adhesion to chemically modified cellulose derivatives (2001) J Mater Sci Mater Med, 12, pp. 543-548; Performance standards for antimicrobial susceptibility testing (2006) Sixteenth informational supplement. Document M100-S16. Wayne, PA: CLSI, , Clinical and Laboratory Standards Institute; Vacheethasanee, K., Temenoff, J.S., Higashi, J.M., Gary, A., Anderson, J.M., Bayston, R., Bacterial surface properties of clinically isolated Staphylococcus epidermidis strains determine adhesion on polyethylene (1998) J Biomed Mater Res, 42, pp. 425-432; Bhat, N.V., Wavhal, D.S., Preparation of cellulose triacetate pervaporation membrane by ammonia plasma treatment (2000) J Appl Polym Sci, 76, pp. 258-265; Amaral, I.F., Granja, P.L., Melo Luis, V., Saramago, B., Barbosa, M.A., Functionalization of chitosan membranes through phosphorylation: atomic force microscopy, wettability, and cytotoxicity studies (2006) J Appl Polym Sci, 102, pp. 276-284; Thomas, M.J.K., Ando, D.J., (1996) Ultraviolet and visible spectroscopy: analytical chemistry by open learning, , Wiley, New York, NY; (1992) High resolution XPS of organic polymers: the Scienta ESCA300 database, , Beamson G., and Briggs D. (Eds), John Wiley & Sons Ltd, Chichester, UK; Yigong Ge, Wikler, M.A., Sahm, D.F., Blosser-Middleton, R.S., Karlowsky, J.A., In vitro antimicrobial activity of doripenem, a new carbapenem (2004) Antimicrob Agents Chemother, 48, pp. 1384-1396; Martínez-Martínez, L., Pascual, A., Giglio, M.I., Perea, E.J., Effect of subinhibitory concentrations of β-lactams on the production of slime, surface hydrophobicity and adhesion of Staphylococcus epidermidis [in Spanish] (1991) Enferm Infecc Microbiol Clin, 9, pp. 543-546
Keywords: Adhesion; Anti-Bacterial Agents; antibacterial activity; Antimicrobial agents; article; Bacterial adhesion; bacterial growth; bacteriostasis; bacterium adherence; Biocompatible Materials; biomaterial; Cellulose; Cellulose triacetate; cilastatin plus imipenem; controlled study; device infection; drug screening; Equipment and Supplies; growth inhibition; Humans; hydrophilicity; Imipenem; in vitro study; infection prevention; Membranes; Microbial Sensitivity Tests; microtiter plate assay; nonhuman; priority journal; Prosthesis-Related Infections; Scanning electron microscopy; Staphylococcus epidermidis; surface property; sustained drug release; X ray photoelectron spectroscopy

Assessment of Disagreement: A New Information-Based Approach - Costa-Santos, C.; Antunes, L.; Souto, A.; Bernardes, J. (Annals of EpidemiologyAnn. Epidemiol., 2010)
Purpose: Disagreement on the interpretation of diagnostic tests and clinical decisions remains an important problem in medicine. As no strategy to assess agreement seems to be fail-safe to compare the degree of agreement, or disagreement, we propose a new information-based approach to assess disagreement. Methods: The sum over all logarithms of possible outcomes of a variable is a valid measure of the amount of information contained in the variable. The proposed measure is based on the amount of information contained in the differences between two observations. This measure is normalized and satisfies the flowing properties: it is a metric, scaled invariant and it has differential weighting. Results: Two real examples and a simulation were used to illustrate the usefulness of the proposed measure to compare the degree of disagreement. Conclusions: Used as complement to the existing methods, we believe our approach can be useful to compare the degree of disagreement among different populations. © 2010 Elsevier Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: ANNPEdoi: 10.1016/j.annepidem.2010.02.011Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Bland, M., (2000) An introduction to medical statistics, , Oxford University Press, Oxford;Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynecology: inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Gow, R.M., Barrowman, N.J., Lai, L., Moher, D., A review of five cardiology journals found that observer variability of measured variables was infrequently reported (2008) J Clin Epidemiol, 61, pp. 394-401; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) J Clin Epidemiol, 58, pp. 215-216; de Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127. , Wiley, Chichester, P. Armitage, T. Colton (Eds.); Shrout, P.E., Fleiss, J.L., Intraclass correlation: uses in assessing rater reliability (1979) Psychol Bull, 88, pp. 420-428; Burdock, E.I., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Psychol Bull, 16, pp. 373-384; McGraw, K.O., Wong, S.P., Forming inferences about some intraclass correlation coefficients (1996) Psychol Methods, 1, pp. 30-46; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Steiner, D.L., Norman, G.R., (2003) Health measurements scales. A practical guide to their development and use, , Oxford University Press, Oxford; Lee, D., Koh, D., Ong, C.N., Statistical evaluation of the agreement between two methods for measuring a quantitative variable (1989) Comput Biol Med, 19, pp. 61-70; Lin, L.K., A concordance correlation coefficient to evaluate reproducibility (1989) Biometrics, 45, pp. 255-268; Nickerson, C.A.E., A note on " A Concordance Correlation Coefficient to Evaluate Reproducibility" (1997) Biometrics, 53, pp. 1503-1507; Atkinson, G., Nevill, A., Comment on the " Use of Concordance Correlation to Assess the Agreement between Two Variables" (1997) Biometrics, 53, pp. 775-777; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Luiz, R.R., Costa, A.J., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: a new graphical approach (2003) J Clin Epidemiol, 56, pp. 963-967; Monti, K.L., Folded empirical distribution function curves-mountain plots (1995) Am Stat, 33, pp. 525-527; Shannon, I., A mathematical theory of communication (1948) Bell System Tech J, 27, pp. 379-423. , 623-656; Bland, J.M., Altaman, D.G., Measuring agreement in method comparison studies (1999) Stat Methods Med Res, 8, pp. 135-160
Keywords: analysis of variance; Apgar score; article; Blood Pressure Determination; blood pressure measurement; correlation coefficient; human; Humans; information science; Information Theory; intermethod comparison; mathematical computing; measurement error; medical research; metric system; Models, Statistical; observer variation; priority journal; probability; process model; reliability; Reproducibility of Results; scale up; standard; Statistical analysis; statistical model; statistics; Statistics as Topic; systolic blood pressure; validity; variance

Bioactivity of immobilized EGF on self-assembled monolayers: Optimization of the immobilization process - Gonçalves, R.; Martins, M.C.L.; Oliveira, M.J.; Almeida-Porada, G.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
Last trends in Biomaterials focus the mimic of cellular environments capable to control cellular responses. Epidermal growth factor (EGF) is a pleiotropic cytokine known to regulate cell proliferation, differentiation, and death. This study aims to optimize the immobilization of EGF on 11-mercapto-1-undecyl-tetra(ethylene)glycol (EG4) - self-assembled monolayers (SAMs) and to establish a new model surface to study EGF-mediated signaling. Gold substrates were modified with a monolayer of EG4 and N,N′- carbonyldiimidazole (CDI) was used to activate hydroxyl terminated groups of EG4-SAMs. EGF was then immobilized on activated EG4-SAMs at pH 7.4, 4°C, and 100 rpm. Different immobilization reaction times were tested as well as different CDI concentrations to optimize the reaction conditions and obtain a range of immobilized EGF concentrations on the surfaces. Surface characterization of EGF-SAMs was performed using radiolabeling, water contact angle measurements, X-ray photoelectron spectroscopy, and ELISA. Phosphorylation of EGFR on BT-20 breast cancer cell line by EGF-SAMs was tested by immunostaining. EGF was successfully immobilized on EG4-SAMs, at 4°C and pH 7.4 in a range of concentrations from 3.6 ± 0.8 to 17.6 ± 1.5 ng/cm 2. The concentration of EGF increases with immobilization time and with the CDI concentration reaching the maximum for surfaces activated with 30 mg/mL of CDI after 48 h. The bioactivity of EGF-SAMs was confirmed by immunostaining of phospho-EGFR of BT-20 cells. This study described EGF immobilization on EG4-SAMs at different concentrations, which could be important surface models to study specific protein interactions at the molecular level evolving EGF-family of proteins. © 2010 Wiley Periodicals, Inc. J.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32723PubMed ID: 20198690Language of Original Document: EnglishCorrespondence Address: Gonçalves, R.; INEB, Biomaterials Division, NEWTherapies Group, R. Campo Alegre, 823, Porto 4150-180, Portugal; email: raquelg@ineb.up.ptChemicals/CAS: epidermal growth factor, 62229-50-9; gold, 7440-57-5; Biocompatible Materials; Epidermal Growth Factor, 62229-50-9; Gold, 7440-57-5; Imidazoles; N,N-carbonyldiimidazole, 530-62-1; Polyethylene Glycols; Receptor, Epidermal Growth Factor, 2.7.10.1; Sulfhydryl CompoundsReferences: Singh, A., Harris, R.C., Autocrine, paracrine and juxtacrine signaling by EGFR ligands (2005) Cell Signal, 17, pp. 1183-1193;Luca, A., Carotenuto, A., Rachiglio, A., Gallo, M., Maiello, M.R., Aldinucci, D.L., Pinto, A., Normanno, N., The role of the EGFR signaling in tumor microenvironment (2008) J Cell Physiol, 214, pp. 559-567; Stenflo, J., Stenberg, Y., Muranyi, A., Calcium-binding EGF-like modules in coagulation proteinases: Function of the calcium ion in module interactions (2000) Biochim Biophys Acta, 1477, pp. 51-63; Leong, K., Karsan, A., Recent insights in the role of notch signaling in tumorigenesis (2006) Blood, 107, pp. 2223-2233; Sakamoto, K., Chao, W.S., Katsube, K.-I., Yamaguchi, A., Distinct roles of EGF repeats for the Notch signaling system (2005) Experimental Cell Research, 302 (2), pp. 281-291. , DOI 10.1016/j.yexcr.2004.09.016, PII S0014482704005658; Savage, C., Hash, J.H., Cohen, S., Epidermal growth factor (1973) J Biol Chem, 248, pp. 7669-7672; Bell, G., Fong, N.M., Stempien, M.M., Wormsted, M.A., Caput, D., Ku, L., Urdea, M.S., Sanchez-Pescador, R., Human epidermal growth factor precursor: cDNA sequence, expression in vitro and gene organization (1986) Nucleic Acids Res, 14, pp. 8427-8446; Carpenter, G., Cohen, S., Epidermal growth factor (1990) J Biol Chem, 265, pp. 7709-7712; Schlessinger, J., Allosteric regulation of epidermal growth factor receptor kinase (1986) J Cell Biol, 103, pp. 2067-2072; Mitamura, T., Higashiyama, S., Taniguchi, N., Klagsbrun, M., Mekada, E., Diphtheria toxin binds to the epidermal growth factor (EGF)-like domain of human heparin-binding EGF-like growth factor/diphtheria toxin receptor and inhibits specifically its mitogenic activity (1995) J Biol Chem, 270, pp. 1015-1019; Wong, R.W.C., Guillaud, L., The role of epidermal growth factor and its receptors in mammalian CNS (2004) Cytokine Growth Factor Rev, 15, pp. 147-156; Mrksich, M., What can surface chemistry do for cell biology? (2002) Curr Opion Chem Biol, 6, pp. 794-797; Tohda, S.K.H., Murakami, N., Sakano, S., Nara, N., Diverse effects of the notch ligands Jagged1 and Delta1 on the growth and differentiation of primary acute myeloblastic leukemia cells (2005) Exp Hematol, 33, pp. 558-563; France, R.M., Short, R.D., Dawson, R.A., MacNeil, S., Attachment of human keratinocytes to plasma co-polymers of acrylic acid/octa-1,7-diene and allyl amine/octa-1,7-diene (1998) Journal of Materials Chemistry, 8 (1), pp. 37-42; Love, J., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Selfassembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Saha, K.P.J., Schaffer, D.V., Healy, K.E., Designing synthetic materials to control stem cell phenotype (2007) Curr Opin Chem Biol, 11, pp. 381-387; Barbosa, J.B.M., Águas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res A, 65, pp. 429-434; Rodrigues, S.N.G.I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Barrias, C., Martins, M.C., Almeida-Porada, G., Barbosa, M.A., Granja, P.L., The correlation between the adsorption of adhesive proteins and cell behaviour on hydroxyl-methyl mixed self-assembled monolayers (2009) Biomaterials, 30, pp. 307-316; Curran, J.M.C.R., Hunt, J.A., The guidance of human mesenchymal stem cell differentiation in vitro by controlled modifications to the cell substrate (2006) Biomaterials, 27, pp. 4783-4793; Lee, M., Brass, D.A., Morris, R., Composto, R.J., Ducheyne, P., The effect of non-specific interactions on cellular adhesion using model surfaces (2005) Biomaterials, 26, pp. 1721-1730; Martins, M.C.L.C.S., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88, pp. 162-173; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Martins, M.C.L.R.B., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl- Terminated self-assebled monolyers (2003) J Biomed Mater Res, 67, pp. 158-171; Barrias, C.C.M.M., Bidarra, S., Sámiranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: Effect of the surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; (1993) Iodine-125. A Guide to Radioiodination Techniques, , Amersham Life Science. Amersham Place, Little Chalfont, Bucks: Amersham International plc; Zhang, J., Matthews, J.M., Ward, L.D., Simpson, R.J., Disruption of the disulfide bonds of recombinant murine interleukin-6 induces formation of a partially unfolded state (1997) Biochemistry, 36, pp. 2380-2389; Solomons, T., (1996) Organic Chemistry, , New York: Wiley; Lukkari, J., Meretoja, M., Kartio, I., Laajalehto, K., Rajamaki, M., Lindstrom, M., Kankare, J., Organic thiosulfates (bunte salts): Novel surface-active sulfur compounds for the preparation of selfassembled monolayers on gold (1999) Langmuir, 15, pp. 3529-3537; Castner, D.G., Hinds, K., Grainger, D.W., X-ray photoelectron spectroscopy sulfur 2p study of organic thiol and bisulfide binding interactions with gold surfaces (1996) Langmuir, 12 (21), pp. 5083-5086; Molina, R., Espinós, J.P., Yubero, F., Erra, P., González-Elipe, A.R., XPS analysis of down stream plasma treated wool: Influence of the nature of the gas on the surface modification of wool (2005) Appl Surf Sci, 252, pp. 1417-1429; Flynn, N., Tran, T.N.T., Cima, M.J., Langer, R., Long-term stability of self-assembled monolayers in biological media (2003) Langmuir, 19, pp. 10909-10915; Willey, T., Vance, A.L., Van Buuren, T., Bostedt, C., Terminello, L.J., Fadley, C.S., Rapid degradation of alkanethiol-based self-assembled monolayers on gold in ambient laboratory conditions (2005) Surf Sci, 576, pp. 188-196; Lage, A., Crombet, T., González, G., Targeting epidermal growth factor receptor signaling: Early results and future trends in oncology (2003) Trends Mol Med, 35, pp. 327-336; Lee, H., Hu, M., Reilly, R.M., Allen, C., Apoptotic epidermal growth factor (EGF)- Conjugated block copolymer micelles as a nanotechnology platform for targeted combination therapy (2007) Mol Pharm, 4, pp. 769-781; Nakaji-Hirabayashi, T., Kato, K., Arima, Y., Iwata, H., Oriented immobilization of epidermal growth factor onto culture substrates for the selective expansion of neural stem cells (2007) Biomaterials, 28, pp. 3517-3529; Stefonek, T., Masters, K.S., Immobilized gradients of epidermal growth factor promote accelerated and directed keratinocyte migration (2007) Wound Repair Regen, 15, pp. 847-855; Ito, Y., Li, J.S., Takahashi, T., Imanishi, Y., Okabayashi, Y., Kido, Y., Kasuga, M., Enhancement of the mitogenic effect by artificial juxtacrine stimulation using immobilized EGF (1997) J Biochem, 121, pp. 514-520; Wang, Q., Bohn, P.W., Surface composition gradients of immobilized cell signaling molecules: Epidermal growth factor on gold (2006) Thin Solid Films, 513, pp. 338-346; Karakecili, A., Satriano, C., Gumusderelioglu, M., Marletta, G., Enhancement of fibroblastic proliferation on chitosan surfaces by immobilized epidermal growth factor (2008) Acta Biomater, 4, pp. 989-996; Hodneland, C., Lee, Y.S., Min, D.H., Mrksich, M., Selective immobilization of proteins to self-assembled monolayers presenting active site-directed capture ligands (2002) PNAS, 99, pp. 5048-5052; Liu, L., Chen, S., Giachelli, C.M., Ratner, B.D., Jiang, S., Controlling osteopontin orientation on surfaces to modulate endothelial cell adhesion (2005) J Biomed Mater Res A, 74, pp. 23-31; Kim, H., Noh, J., Hara, M., Lee, H., Characterization of mixed selfassembled monolayers for immobilization of streptavidin using chemical force microscopy (2008) Ultramicroscopy, 108, pp. 1140-1143; Delamarche, E., Sundarababu, G., Biebuyck, H., Michel, B., Gerber, Ch., Sigrist, H., Wolf, H., Mathieu, H.J., Immobilization of antibodies on a photoactive self-assembled monolayer on gold (1996) Langmuir, 12 (8), pp. 1997-2006; Gonçalves, R., Martins, M.C.L., Almeida-Porada, G., Barbosa, M.A., Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers (2009) Biomaterials, 30, pp. 6879-6887; Mrksich, M., Whitesides, G.M., Using Self-Assembled Monolayers That Present Oligo(ethylene glycol) Groups to Control the Interactions of Proteins with Surfaces (1997) ACS Symposium Series, 680, pp. 361-373; Chen, G., Ito, Y., Gradient micropattern immobilization of EGF to investigate the effect of artificil juxtacrine stimulation (2001) Biomaterials, 22, pp. 2453-2457; Allewood, D., Nielsen, K., Alewwod, P.F., Craik, D.J., Andrews, P., Nerrie, M., White, S., Nice, E.C., The role of disulfide bonds in the structure and function of murine epidermal growth factor (mEGF) (2005) Growth Factors, 23, pp. 97-110; Morton, R., Mangroo, D., Gerber, G.E., A novel method of complete activation by carbonyldiimidazole: Application to esther synthesis (1988) Can J Chem, 66, pp. 1701-1705; Stollner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304, pp. 157-165; Crowley, S.C., Chan, K.C., Walters, R.R., Optimization of protein immobilization on 1,1′-carbonyldiimidazole- activated diol-bonded silica (1986) J Chromatogr A, 359, pp. 359-368; Mateus, A., Seruca, R., Machado, J.C., Keller, G., Oliveira, M.J., Suriano, G., Luber, B., EGFR regulates RhoA-GTP dependent cell motility in E-cadherin mutant cells (2007) Hum Mol Genet, 16, pp. 1639-1647; Garcia, R., Franklin, R.A., Mccubrey, J.A., EGF induces cell motility and multi-drug resistance gene expression in breast cancer cells (2006) Cell Cycle, 5, pp. 2820-2826
Keywords: Adsorption; Angle measurement; article; Biocompatible Materials; Biological materials; Breast cancer cells; cancer cell culture; Carbonyldiimidazole; Cell culture; Cell immobilization; Cell Line, Tumor; cell proliferation; Cellular environment; Cellular response; Concentration (process); Concentration of; Contact angle; controlled study; Cytokines; EGF; Electron energy levels; enzyme linked immunosorbent assay; Enzyme-Linked Immunosorbent Assay; epidermal growth factor; Epidermal growth factors; Ethylene; Glycols; gold; Gold substrates; human; human cell; Humans; Hydroxyl-terminated; Imidazoles; Immobilization process; Immobilization reaction; immunofluorescence; immunohistochemistry; Immunostaining; Molecular levels; Nanostructured materials; Nanostructured surface; Nanostructured surfaces; New model; Optimization; Phosphorylation; Photoelectron spectroscopy; Polyethylene Glycols; Protein adsorption; protein immobilization; protein interaction; protein phosphorylation; Proteins; Radiolabeling; Radioligand Assay; Reaction conditions; reaction optimization; Receptor, Epidermal Growth Factor; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Sulfhydryl Compounds; Surface characterization; Surface functionalization; Surface models; Surface Properties; Water contact angle measurement; X ray photoelectron spectroscopy

Biocompatibility and calcification of bovine pericardium employed for the construction of cardiac bioprostheses treated with different chemical crosslink methods - Jorge-Herrero, E.; Fonseca, C.; Barge, A.P.; Turnay, J.; Olmo, N.; Fernández, P.; Lizarbe, M.A.; García Páez, J.M. (Artificial OrgansArtif. Organs, 2010)
The use of biological materials in the construction of bioprostheses requires the application of different chemical procedures to improve the durability of the material without producing any undesirable effects. A number of crosslinking methods have been tested in biological tissues composed mainly of collagen. The aim of this study was to evaluate the in vitro biocompatibility, the mechanical properties, and in vivo calcification of chemically modified bovine pericardium using glutaraldehyde acetals (GAAs) in comparison with glutaraldehyde (GA) treatment. Homsy's tests showed that the most cytotoxic treatment is GA whereas GAA treatments showed lower cytotoxicity. Regarding the mechanical properties of the modified materials, no significant differences in stress at rupture were detected among the different treatments. Zeta-Potential showed higher negative values for GA treatment (-4.9 ± 0.6 mV) compared with GAA-0.625% (-2.2 ± 0.5 mV) and GAA-1% (-2.2 ± 0.4 mV), which presented values similar to native tissue. Similar results were obtained for calcium permeability coefficients which showed the highest values for GA treatment (0.12 ± 0.02 mm 2/min), being significantly lower for GAA treatments or non-crosslinked pericardium. These results confirmed the higher propensity of the GA-treated tissues for attraction of calcium cations and were in good agreement with the calcification degree obtained after 60 days implantation into young rats, which was significantly higher for the GA group (22.70 ± 20.80 mg/g dry tissue) compared with GAA-0.625% and GAA-1% groups (0.49 ± 0.28 mg/g dry tissue and 3.51 ± 3.27 mg/g dry tissue, respectively; P < 0.001). In conclusion, GAA treatments can be considered a promising alternative to GA treatment. © 2010, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: ARORDdoi: 10.1111/j.1525-1594.2009.00978.xPubMed ID: 20633147Language of Original Document: EnglishCorrespondence Address: Jorge-Herrero, E.; Biomateriales y Telemedicina, Hospital Universitario Puerta de Hierro Majadahonda, Peine 7, planta 0, c/ Manuel de Falla 2, 28222Majadahonda, Madrid, Spain; email: ejorge.herrero@bioing.cph.esChemicals/CAS: calcium, 14092-94-5, 7440-70-2; glutaraldehyde, 111-30-8, 37245-61-7; Calcium, 7440-70-2; Cross-Linking Reagents; Glutaral, 111-30-8References: Grunkemeier, G.L., Rahimtoola, S.H., Artificial heart valves (1990) Annu Rev Med, 41, pp. 251-263;Vongpatanasin, W., Hillis, L.D., Lange, R.A., Prosthetic heart valves (1996) N Engl J Med, 335, pp. 407-416; Zilla, P., Brink, J., Human, P., Bezuidenhout, D., Prosthetic heart valves: Catering for the few (2008) Biomaterials, 29, pp. 385-406; Schoen, F.J., Levy, R.J., Heart valve bioprostheses: Antimineralization (1992) Eur J Cardiothorac Surg, 6 (1), pp. 91-3. , Suppl; Schoen, F.J., Cardiac valve prostheses: Review of clinical status and contemporary biomaterials issues (1987) J Biomed Mater Res, 21 (A1), pp. 91-117. , Suppl; Thubrikar, M.J., Deck, J.D., Aouad, J., Nolan, S.P., Role of mechanical stress in calcification of aortic bioprosthetic valves (1983) J Thorac Cardiovasc Surg, 86, pp. 115-125; Schoen, F.J., Kujovich, J.L., Levy, R.J., Sutton, M.S., Bioprosthetic valve failure (1988) Cardiovasc Clin, 18, pp. 289-317; Schoen, F.J., Tsao, J.W., Levy, R.J., Calcification of bovine pericardium used in cardiac valve bioprostheses. Implications for the mechanisms of bioprosthetic tissue mineralization (1986) Am J Pathol, 123, pp. 134-145; Ishihara, T., Ferrans, V.J., Boyce, S.W., Jones, M., Roberts, W.C., Structure and classification of cuspal tears and perforations in porcine bioprosthetic cardiac valves implanted in patients (1981) Am J Cardiol, 48, pp. 665-678; Gendler, E., Gendler, S., Nimni, M.E., Toxic reactions evoked by glutaraldehyde-fixed pericardium and cardiac valve tissue bioprosthesis (1984) J Biomed Mater Res, 18, pp. 727-736; Chanda, J., Kondoh, K., Ijima, K., Matsukawa, M., Kuribayashi, R., In vitro and in vivo calcification of vascular bioprostheses (1998) Biomaterials, 19, pp. 1651-1656; Biedrzycki, L.M., Lerner, E., Levy, R.J., Schoen, F.J., Differential calcification of cusps and aortic wall failed stented porcine bioprosthetic valves (1997) J Biomed Mater Res, 34, pp. 411-415; Jorge, H.E., Fernandez, P., Gutierrez, M., Castillo, O.J., Study of the calcification of bovine pericardium: Analysis of the implication of lipids and proteoglycans (1991) Biomaterials, 12, pp. 683-689; Arenaz, B., Maestro, M.M., Fernandez, P., Effects of periodate and chondroitin 4-sulfate on proteoglycan stabilization of ostrich pericardium. Inhibition of calcification in subcutaneous implants in rats (2004) Biomaterials, 25, pp. 3359-3368; Calero, P., Jorge-Herrero, E., Turnay, J., Gelatinases in soft tissue biomaterials. Analysis of different crosslinking agents (2002) Biomaterials, 23, pp. 3473-3478; Simionescu, A., Simionescu, D., Deac, R.F., Matrix metalloproteinases in the pathology of natural and bioprosthetic cardiac valves (1996) Cardiovasc Pathol, 5, pp. 323-332; Griffiths, L.G., Choe, L.H., Reardon, K.F., Dow, S.W., Christopher, O.E., Immunoproteomic identification of bovine pericardium xenoantigens (2008) Biomaterials, 29, pp. 3514-3520; Vesely, I., Barber, J.E., Ratliff, N.B., Tissue damage and calcification may be independent mechanisms of bioprosthetic heart valve failure (2001) J Heart Valve Dis, 10, pp. 471-477; Vesely, I., The evolution of bioprosthetic heart valve design and its impact on durability (2003) Cardiovasc Pathol, 12, pp. 277-286; Jorge-Herrero, E., Fernandez, P., De La Torre, N., Inhibition of the calcification of porcine valve tissue by selective lipid removal (1994) Biomaterials, 15, pp. 815-820; Pettenazzo, E., Valente, M., Thiene, G., Octanediol treatment of glutaraldehyde fixed bovine pericardium: Evidence of anticalcification efficacy in the subcutaneous rat model (2008) Eur J Cardiothorac Surg, 34, pp. 418-422; Nimni, M.E., Myers, D., Ertl, D., Han, B., Factors which affect the calcification of tissue-derived bioprostheses (1997) J Biomed Mater Res, 35, pp. 531-537; Jayakrishnan, A., Jameela, S.R., Glutaraldehyde as a fixative in bioprostheses and drug delivery matrices (1996) Biomaterials, 17, pp. 471-484; Eybl, E., Griesmacher, A., Grimm, M., Wolner, E., Toxic effects of aldehydes released from fixed pericardium on bovine aortic endothelial cells (1989) J Biomed Mater Res, 23, pp. 1355-1365; Levy, R.J., Schoen, F.J., Sherman, F.S., Nichols, J., Hawley, M.A., Lund, S.A., Calcification of subcutaneously implanted type i collagen sponges. Effects of formaldehyde and glutaraldehyde pretreatments (1986) Am J Pathol, 122, pp. 71-82; Golomb, G., Schoen, F.J., Smith, M.S., Linden, J., Dixon, M., Levy, R.J., The role of glutaraldehyde-induced cross-links in calcification of bovine pericardium used in cardiac valve bioprostheses (1987) Am J Pathol, 127, pp. 122-130; Huang-Lee, L.L., Cheung, D.T., Nimni, M.E., Biochemical changes and cytotoxicity associated with the degradation of polymeric glutaraldehyde derived crosslinks (1990) J Biomed Mater Res, 24, pp. 1185-1201; Southern, L.J., Hughes, H., Lawford, P.V., Clench, M.R., Manning, N.J., Glutaraldehyde-induced cross-links: A study of model compounds and commercial bioprosthetic valves (2000) J Heart Valve Dis, 9, pp. 241-248; Goissis, G., Yoshioka, S.A., Braile, D.M., Ramirez, V.D., The chemical protecting group concept applied in crosslinking of natural tissues with glutaraldehyde acetals (1998) Artif Organs, 22, pp. 210-214; Yoshioka, S.A., Goissis, G., Thermal and spectrophotometric studies of new crosslinking method for collagen matrix with glutaraldehyde acetals (2008) J Mater Sci Mater Med, 19, pp. 1215-1223; Vyavahare, N.R., Hirsch, D., Lerner, E., Prevention of calcification of glutaraldehyde-crosslinked porcine aortic cusp by ethanol preincubation: Mechanistic studies of protein structure and water-biomaterial relationship (1998) J Biomed Mater Res, 40, pp. 577-585; Triglia, D., Braa, S.S., Yonan, C., Naughton, G.K., In vitro toxicity of various classes of test agents using the neutral red assay on a human three-dimensional physiologic skin model (1991) Vitro Cell Dev Biol, 27, pp. 239-244; Plumb, J.A., Milroy, R., Kaye, S.B., Effects of the pH dependence of 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyl-tetrazolium bromide-formazan absorption on chemosensitivity determined by a novel tetrazolium-based assay (1989) Cancer Res, 49, pp. 4435-4440; Garcia Paez, J.M., Carrera, A., Cordon, A., Uniaxial and biaxial tensile strength of calf pericardium used in the construction of bioprostheses: Biomaterial selection criteria (2000) J Biomater Appl, 15, pp. 47-64; Kirby, B.J., Hasselbrink, Jr.E.F., Zeta potential of microfluidic substrates: 2. Data for polymers (2004) Electrophoresis, 25, pp. 203-213; Jorge-Herrero, E., Turnay, J., Calero, P., Calcification and identification of metalloproteinases in bovine pericardium after subcutaneous implantation in rats (2001) J Mater Sci Mater Med, 12, pp. 1013-1017; Van Wachem, P.B., Van Luyn, M.J.A., Damink, L.H.H.O., Dijkstra, P.J., Feijen, J., Nieuwenhuis, P., Tissue regenerating capacity of carbodiimide-crosslinked dermal sheep collagen during repair of the abdominal wall (1994) International Journal of Artificial Organs, 17 (4), pp. 230-239; Olde Damink, L.H.H., Dijkstra, P.J., Van Luyn, M.J.A., Van Wachem, P.B., Nieuwenhuis, P., Feijen, J., In vitro degradation of dermal sheep collagen cross-linked using a water-soluble carbodiimide (1996) Biomaterials, 17 (7), pp. 679-684. , DOI 10.1016/0142-9612(96)86737-8; Olde Damink, L.H., Dijkstra, P.J., Van Luyn, M.J., Van Wachem, P.B., Nieuwenhuis, P., Feijen, J., Cross-linking of dermal sheep collagen using a water-soluble carbodiimide (1996) Biomaterials, 17, pp. 765-773; Olde Damink, L.H.H., Dijkstra, P.J., Van Luyn, M.J.A., Van Wachem, P.B., Nieuwenhuis, P., Feijen, J., In vitro degradation of dermal sheep collagen cross-linked using a water-soluble carbodiimide (1996) Biomaterials, 17 (7), pp. 679-684. , DOI 10.1016/0142-9612(96)86737-8; Anselme, K., Petite, H., Herbage, D., Inhibition of calcification in vivo by acyl azide cross-linking of a collagen-glycosaminoglycan sponge (1992) Matrix, 12, pp. 264-273; Petite, H., Frei, V., Huc, A., Herbage, D., Use of diphenylphosphorylazide for cross-linking collagen-based biomaterials (1994) J Biomed Mater Res, 28, pp. 159-165; Petite, H., Duval, J.L., Frei, V., Abdul-Malak, N., Sigot-Luizard, M.F., Herbage, D., Cytocompatibility of calf pericardium treated by glutaraldehyde and by the acyl azide methods in an organotypic culture model (1995) Biomaterials, 16, pp. 1003-1008; Marinucci, L., Lilli, C., Guerra, M., Biocompatibility of collagen membranes crosslinked with glutaraldehyde or diphenylphosphoryl azide: An in vitro study (2003) J Biomed Mater Res, 67, pp. 504-509; Naimark, W.A., Pereira, C.A., Tsang, K., Lee, J.M., HMDC crosslinking of bovine pericardial tissue: A potential role of the solvent environment in the design of bioprosthetic materials (1995) J Mater Sci Mater Med, 6, pp. 235-241; Khouw, I.M., Van Wachem, P.B., Molema, G., Plantinga, J.A., De Leij, L.F., Van Luyn, M.J., The foreign body reaction to a biodegradable biomaterial differs between rats and mice (2000) J Biomed Mater Res, 52, pp. 439-446; Huma, P., Bezuidenhout, D., Torrianni, M., Hendriks, M., Zilla, P., Optimization of diamine bridges in glutaraldehyde treated bioprosthetic aortic wall tissue (2002) Biomaterials, 23, pp. 2099-2103; Jorge-Herrero, E., Fernandez, P., Turnay, J., Influence of different chemical cross-linking treatments on the properties of bovine pericardium and collagen (1999) Biomaterials, 20, pp. 539-545
Keywords: acetal derivative; animal cell; animal experiment; animal tissue; Animals; article; Biocompatibility; Bioprostheses; Bioprosthesis; Bovinae; Calcification; Calcification, Physiologic; Calcium; cation; Cattle; Chemical modification; controlled study; Cross-Linking Reagents; Crosslinking; Cytotoxicity; Glutaral; glutaraldehyde; heart valve bioprosthesis; Heart, Artificial; in vitro study; materials testing; mechanical stress; nonhuman; pericardium; permeability; priority journal; rat; Rats; Rattus; Subcutaneous implantation; Tissue engineering; Zeta potential

Cell nuclei and cytoplasm joint segmentation using the sliding band filter - Quelhas, P.; Marcuzzo, M.; Mendonça, A.M.; Campilho, A. (IEEE Transactions on Medical ImagingIEEE Trans. Med. Imaging, 2010)
Microscopy cell image analysis is a fundamental tool for biological research. In particular, multivariate fluorescence microscopy is used to observe different aspects of cells in cultures. It is still common practice to perform analysis tasks by visual inspection of individual cells which is time consuming, exhausting and prone to induce subjective bias. This makes automatic cell image analysis essential for large scale, objective studies of cell cultures. Traditionally the task of automatic cell analysis is approached through the use of image segmentation methods for extraction of cells' locations and shapes. Image segmentation, although fundamental, is neither an easy task in computer vision nor is it robust to image quality changes. This makes image segmentation for cell detection semi-automated requiring frequent tuning of parameters. We introduce a new approach for cell detection and shape estimation in multivariate images based on the sliding band filter (SBF). This filter's design makes it adequate to detect overall convex shapes and as such it performs well for cell detection. Furthermore, the parameters involved are intuitive as they are directly related to the expected cell size. Using the SBF filter we detect cells' nucleus and cytoplasm location and shapes. Based on the assumption that each cell has the same approximate shape center in both nuclei and cytoplasm fluorescence channels, we guide cytoplasm shape estimation by the nuclear detections improving performance and reducing errors. Then we validate cell detection by gathering evidence from nuclei and cytoplasm channels. Additionally, we include overlap correction and shape regularization steps which further improve the estimated cell shapes. The approach is evaluated using two datasets with different types of data: a 20 images benchmark set of simulated cell culture images, containing 1000 simulated cells; a 16 images Drosophila melanogaster Kc167 dataset containing 1255 cells, stained for DNA and actin. Both image datasets present a difficult problem due to the high variability of cell shapes and frequent cluster overlap between cells. On the Drosophila dataset our approach achieved a precision/recall of 95%/69% and 82%/90% for nuclei and cytoplasm detection respectively and an overall accuracy of 76%. © 2010 IEEE.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusArt. No.: 5477157CODEN: ITMIDdoi: 10.1109/TMI.2010.2048253Language of Original Document: EnglishCorrespondence Address: Quelhas, P.; Instituto de Engenharia Biomédica (INEB), 4200-465 Porto, Portugal; email: pedro.quelhas@gmail.comChemicals/CAS: DNA, 9007-49-2; Actins; DNA, 9007-49-2References: Bleau, A., Leon, L., Watershed-based segmentation and region merging (2000) Comput. Vis. Image Understand., 77 (3), pp. 317-370;Clocksin, W., Automatic segmentation of overlapping nuclei with high background variation using robust estimation and flexible contour models (2003) Proc. 12th Int. Conf. Image Anal. Process., pp. 682-687; Cloppet, F., Boucher, A., Segmentation of overlapping/aggregating nuclei cells in biological images (2008) Proc. 19th Int. Conf. Pattern Recognit. (ICPR 2008), pp. 1-4; Danek, O., Matula, P., De Solorzano, C.O., Munoz-Barrutia, A., Maska, M., Kozubek, M., Segmentation of touching cell nuclei using a two-stage graph cut model (2009) LNCS, 5575, pp. 410-419. , Proc. SCIA; Fok, Y., Chan, J., Chin, R., Automated analysis of nerve-cell images using active contour models (1996) IEEE Trans. Med. Imag., 15 (3), pp. 353-368. , Jun; Harder, N., M-Bermudez, F., Godinez, W., Ellenberg, J., Eils, R., Rohr, K., Automated analysis of mitotic cell nuclei in 3-D fluorescence microscopy image sequences (2008) Workshop Bio-Image Inf.: Biol. Imag., Comput. Vis. Data Mining, pp. 17-18. , Santa Barbara, CA; Hill, A., Lapan, P., Li, Y., Haney, S., Impact of image segmentation on high-content screening data quality for sk-br-3 cells (2007) BMC Bioin-formatics, 8 (340), pp. 1-13; Hu, M., Ping, X., Ding, Y., A new active contour model and its application on cell segmentation (2004) 2004 8th International Conference on Control, Automation, Robotics and Vision (ICARCV), 2, pp. 1104-1107. , TuA7.09 - P0673, 2004 8th International Conference on Control, Automation, Robotics and Vision (ICARCV); Jones, T.R., Carpenter, A., Golland, P., Voronoi-based segmentation of cells on image manifolds (2005) ICCV Workshop Comput. Vis. Biomed. Image Appl. (CVBIA), pp. 535-543; Klemencic, A., Kovacic, S., Pernus, F., Automated segmentation of muscle fiber images using active contour models (1998) Cytometry, 32, pp. 317-326; Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Trans. Image Process., 8 (8), pp. 1029-1038. , Aug; Lehmussola, A., Ruusuvuori, P., Selinummi, J., Huttunen, H., Yli-Harja, O., Computational framework for simulating fluorescence microscope images with cell populations (2007) IEEE Trans. Med. Imag., 26 (7), pp. 1010-1016. , Jul; Luc, V., Soille, P., Watersheds in digital spaces: An efficient algorithm based on immersion simulations (1991) IEEE Trans. Pattern Anal. Mach. Intell., 13 (6), pp. 583-598. , Jun; Marcuzzo, M., Guichard, T., Quelhas, P., Mendonça, A.M., Campilho, A., Cell division detection on the arabidopsis thaliana root (2009) LNCS, 5524, pp. 168-175. , Proceedings of IbPRIA. New York: Springer; Marcuzzo, M., Quelhas, P., Mendonça, A.M., Campilho, A., Evaluation of symmetry enhanced sliding band filter for plant cell nuclei detection in low contrast noisy fluorescent images (2009) LNCS, 5627, pp. 824-831. , Proceedings of ICIAR. New York: Springer; Moore, P., Molloy, D., A survey of computer-based deformable models (2007) Int. Mach. Vis. Image Process. Conf. (IMVIP), pp. 55-66; Otsu, N., A threshold selection method from gray-level histograms (1979) IEEE Tran. Syst., Man, Cybern., 9 (1), pp. 62-66. , Jan; Pereira, C.S., Fernandes, H., Mendonça, A.M., Campilho, A., Detection of lung nodule candidates in chest radiographs (2007) LNCS, 4478, pp. 170-177; Pereira, C.S., Mendonça, A.M., Campilho, A., Evaluation of contrast enhancement filters for lung nodule detection Proceedings of ICIAR. New York: Springer, 4633, pp. 878-888; Quelhas, P., Marcuzzo, M., Oliveira, M.J., Mendonça, A.M., Campilho, A., Cancer cell detection and invasion depth estimation in brightfield images (2009) Proc. 20th Br. Mach. Vis. Conf. (BMVC), , London, U.K; Ruusuvuori, P., Lehmussola, A., Selinummi, J., Rajala, T., Huttunen, H., Yli-Harja, O., Benchmark set of synthetic images for validating cell image analysis algorithms (2008) Proc. 16th Eur. Signal Process. Conf., , Lausanne, Switzerland; Solorzano, C., Malladi, R., Lelievre, S., Lockett, S., Segmentation of nuclei and cells using membrane related protein markers (2001) J. Microscopy, 201, pp. 404-415; Tek, F.B., Dempster, A.G., Kale, I., (2006) Mathematical Morphology:40 Years on, 30, pp. 441-454. , New York: Springer; Wei, J., Hagihara, Y., Kobatake, H., Detection of rounded opacities on chest radiographs using convergence index filter (1999) Proc. Int. Conf. Image Anal. Process., pp. 757-761; Xiong, G., Zhou, X., Ji, L., Bradley, P., Perrimon, N., Wong, S., Segmentation of drosophila RNAI fluorescence images using level sets (2006) Proc. IEEE Int. Conf. Image Process., pp. 73-76; Xiong, G., Zhou, X., Ji, L., Automated segmentation of drosophila RNAi fluorescence cellular images using deformable models (2006) IEEE Trans. Circ. Syst. i, 53 (11), pp. 2415-2424. , Nov; Yan, P., Zhou, X., Shah, M., Wong, S.T.C., Automatic segmentation of high-throughput RNAi fluorescent cellular images (2008) IEEE Trans. Inf. Technol. Biomed., 12 (1), pp. 109-117. , Jan; Yang, X., Li, H., Zhou, X., Nuclei segmentation using marker-controlled watershed, tracking using mean-shift, and kalman filter in time-lapse microscopy (2006) IEEE Trans. Circuits Syst., 53 (11), pp. 2405-2414. , Nov
Keywords: actin; Actins; animal; Animals; article; Band filters; Biological research; cell aggregation; Cell analysis; Cell culture; Cell detection; Cell images; cell nucleus; Cell segmentation; Cell Shape; Cell shapes; Cell size; Cells; chemistry; Computer vision; Convergence filters; Convex shapes; cytoplasm; Data sets; Databases, Factual; Digital image storage; DNA; Drosophila melanogaster; factual database; Fluorescence; Fluorescence microscopy; Fundamental tools; High variability; Image analysis; Image datasets; image processing; image processing in biology; Image Processing, Computer-Assisted; Image quality; Image segmentation; Imaging systems; Improving performance; Individual cells; Joint segmentation; Location; methodology; Microscopy, Fluorescence; Multivariate analysis; multivariate image processing; New approaches; Nuclear detection; Overlap correction; reproducibility; Reproducibility of Results; Semi-automated; Shape estimation; Shape regularization; ultrastructure; Visual communication; Visual inspection

Ceramics for dental restorations - an introduction - Santander, S.A.; Vargas, A.P.; Escobar, J.S.; Monteiro, F.J.; Tamayo, L.F.R. (Una perspectiva de las cerámicas para restauraciones dentalesDYNADYNA, 2010)
Dental ceramics are the preferred materials for oral restoration due to some characteristics, such as adequate esthetics, high fracture strength and chemical stability. Currently, dental professionals have a large amount of ceramic systems to choose from, all of them having small differences regarding their chemistry, processing temperatures, mechanical strength and clinical applications. These differences lead to classification systems that are difficult to understand by professionals outside the dental field. The aim of this work is to review the current dental ceramic systems and present them from a compositional perspective to assure the comprehension of these materials by professionals who belong to the Biomedical Engineering field. A great effort was made to avoid classification methods imposed by manufacturers and to obtain a quick compilation of available information from the literature allowing the reader to have a general view of the stateoftheart on dental ceramics.
Keywords: Ceramic systems; Feldspathic porcelain; Glassceramics; Leucite; Mechanical and physical properties; Zirconium oxide

Characterization of polymeric solutions as injectable vehicles for hydroxyapatite microspheres - Oliveira, S.M.; Almeida, I.F.; Costa, P.C.; Barrias, C.C.; Ferreira, M.R.P.; Bahia, M.F.; Barbosa, M.A. (AAPS PharmSciTechAAPS PharmSciTech, 2010)
A polymeric solution and a reinforcement phase can work as an injectable material to fill up bone defects. However, the properties of the solution should be suitable to enable the transport of that extra phase. Additionally, the use of biocompatible materials is a requirement for tissue regeneration. Thus, we intended to optimize a biocompatible polymeric solution able to carry hydroxyapatite microspheres into bone defects using an orthopedic injectable device. To achieve that goal, polymers usually regarded as biocompatible were selected, namely sodium carboxymethylcellulose, hydroxypropylmethylcellulose, and Na-alginate (ALG). The rheological properties of the polymeric solutions at different concentrations were assessed by viscosimetry before and after moist heat sterilization. In order to correlate rheological properties with injectability, solutions were tested using an orthopedic device applied for minimal invasive surgeries. Among the three polymers, ALG solutions presented the most suitable properties for our goal and a non-sterile ALG 6% solution was successfully used to perform preliminary injection tests of hydroxyapatite microspheres. Sterile ALG 7.25% solution was found to closely match non-sterile ALG 6% properties and it was selected as the optimal vehicle. Finally, sterile ALG 7.25% physical stability was studied at different temperatures over a 3-month period. It was observed that its rheological properties presented minor changes when stored at 25°C or at 4°C. © 2010 American Association of Pharmaceutical Scientists.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1208/s12249-010-9447-3PubMed ID: 20490958Language of Original Document: EnglishCorrespondence Address: Oliveira, S. M.; Dep. de Eng. Mecânica e Gestão Industrial, Escola Superior de Tecnologia e Gestão de Viseu, Campus Politécnico de Repeses, 3504-510, Viseu, Portugal; email: soliveira@estv.ipv.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; carboxymethylcellulose, 8050-38-2, 9000-11-7, 9004-32-4, 9050-04-8; hydroxyapatite, 1306-06-5, 51198-94-8; hydroxypropylmethylcellulose, 9004-65-3; Biocompatible Materials; Capsules; Durapatite, 1306-06-5; Excipients; Polymers; Solutions; VehiclesReferences: Verlaan, J.J., Oner, F.C., Dhert, W.J., Anterior spinal column augmentation with injectable bone cements (2006) Biomat, 27 (3), pp. 290-301;Chenite, A., Chaput, C., Wang, D., Combes, C., Buschmann, M.D., Hoemann, C.D., Novel injectable neutral solutions of chitosan form biodegradable gels in situ (2000) Biomat, 21 (21), pp. 2155-2161; Hoemann, C.D., Sun, J., Legare, A., McKee, M.D., Buschmann, M.D., Tissue engineering of cartilage using an injectable and adhesive chitosan-based cell-delivery vehicle (2005) Osteoarthritis Cart., 13 (4), pp. 318-329; Balakrishnan, B., Jayakrishnan, A., Self-cross-linking biopolymers as injectable in situ forming biodegradable scaffolds (2005) Biomat, 26 (18), pp. 3941-3951; Shu, X.Z., Ghosh, K., Liu, Y., Palumbo, F.S., Luo, Y., Clark, R.A., Attachment and spreading of fibroblasts on an RGD peptidemodified injectable hyaluronan hydrogel (2004) J. Biomed. Mater. Res., 68 A (2), pp. 365-375; Shu, X.Z., Ahmad, S., Liu, Y., Prestwich, G.D., Synthesis and evaluation of injectable, in situ crosslinkable synthetic extracellular matrices for tissue engineering (2006) J. Biomed. Mater. Res. A, 79 (4), pp. 902-912; Weiss, P., Gauthier, O., Bouler, J.-M., Grimandi, G., Daculsi, G., Injectable bone substitute using a hydrophilic polymer (1999) Bone, 25 (SUPPL. 1), pp. 67S-70S. , DOI 10.1016/S8756-3282(99)00146-5, PII S8756328299001465; Trojani, C., Weiss, P., Michiels, J.F., Vinatier, C., Guicheux, J., Daculsi, G., Three-dimensional culture and differentiation of human osteogenic cells in an injectable hydroxypropylmethylcellulose hydrogel (2005) Biomat, 26 (27), pp. 5509-5517; Virto, M.R., Frutos, P., Torrado, S., Frutos, G., Gentamicin release from modified acrylic bone cements with lactose and hydroxypropylmethylcellulose (2003) Biomat, 24 (1), pp. 79-87; Bodic, F., Amouriq, Y., Gayet-Delacroix, M., Gauthier, O., Bouler, J.-M., Daculsi, G., Méthode nom invasive d'evaluation d'un substitut osseux injectable/Non-invasive evaluation of an injectable bone substitute (2002) C R Biologies, 325, pp. 345-353; Andrews, G.P., Gorman, S.P., Jones, D.S., Rheological characterisation of primary and binary interactive bioadhesive gels composed of cellulose derivatives designed as ophthalmic viscosurgical devices (2005) Biomat, 26 (5), pp. 571-580; He, S., Yaszemski, M.J., Yasko, A.W., Engel, P.S., Mikos, A.G., Injectable biodegradable polymer composites based on poly (propylene fumarate) crosslinked with poly (ethylene glycol) dimethacrylate (2000) Biomat, 21 (23), pp. 2389-2394; Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomat, 21 (23), pp. 2405-2412; Iooss, P., Le Ray, A.M., Grimandi, G., Daculsi, G., Merle, C., A new injectable bone substitute combining poly (epsilon-caprolactone) microparticles with biphasic calcium phosphate granules (2001) Biomat, 22 (20), pp. 2785-2794; Uda, H., Sugawara, Y., Nakasu, M., Experimental studies on hydroxyapatite powder-carboxymethyl chitin composite: Injectable material for bone augmentation (2006) J. Plast. Reconstr. Aesthet. Surg., 59 (2), pp. 188-196; Carrodeguas, R.G., Lasa, B.V., Barrio, J.S.D., Injectable acrylic bone cements for vertebroplasty with improved properties (2004) J. Biomed. Mater. Res. B-Appl. Biomat., 68 (1), pp. 94-104; Oliveira, S.M., Barrias, C.C., Ribeiro, C.C., Almeida, I.F., Bahia, M.F., Barbosa, M.A., Morphology and mechanical properties of injectable ceramic microspheres (2009) Key Engineering Mat., 396-398, pp. 691-694; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Key Engineering Mat., 254-256, pp. 877-880; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Preparation and characterisation of calcium-phosphate porous microspheres with a uniform size for biomedical applications (2006) J. Mater. Sci. Mater. Med., 17 (5), pp. 455-463; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Ferreira, M.P., Bahia, M.F., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gelforming ability (2008) J. Biomed. Mater. Res. B-Appl. Biomat., 87 B, pp. 49-58; Barnes, H.A., Hutton, J.F., Walters, K., (1998) An Introduction to Rheology, , Amsterdam: Elsevier Science; Leo, W.J., McLoughlin, A.J., Malone, D.M., Effects of sterilization treatments on some properties of alginate solutions and gels (1990) Biotech. Progress, 6 (1), pp. 51-53; Holme, H.K., Lindmo, K., Kristiansen, A., Smidsrød, O., Thermal depolymerization of alginate in the solid state (2003) Carbohydrate Polym., 54 (4), pp. 431-438; Bohner, M., Baroud, G., Injectability of calcium phosphate pastes (2005) Biomat, 26 (13), pp. 1553-1563; Hide, I.G., Gangi, A., Percutaneous vertebroplasty: History, technique and current perspectives (2004) Clin. Radiol., 59 (6), pp. 461-467; Lewis, G., Injectable bone cements for use in vertebroplasty and kyphoplasty: State-of-the-art review (2006) J. Biomed. Mat. Res. B-Appl. Biomat., 76 B (2), pp. 456-468; Baumann, A., Tauss, J., Baumann, G., Tomka, M., Hessinger, M., Tiesenhausen, K., Cement embolization into the vena cava and pulmonal arteries after vertebroplasty: Interdisciplinary management (2006) Europ J. Vasc. and End Surg., 31 (5), pp. 558-561; Mathis, J.M., Wong, W., Percutaneous vertebroplasty: Technical considerations (2003) J. Vasc. and Intervent Rad., 14 (8), pp. 953-960; Xu, H.H., Weir, M.D., Burguera, E.F., Fraser, A.M., Injectable and macroporous calcium phosphate cement scaffold (2006) Biomat, 27 (24), pp. 4279-4287; Gisep, A., Curtis, R., Hanni, M., Suhm, N., Augmentation of implant purchase with bone cements: An in vitro study of injectability and dough distribution (2006) J. Biomed. Mater. Res. B-Appl. Biomat., 77 (1), pp. 114-119; Krebs, J., Ferguson, S.J., Bohner, M., Baroud, G., Steffen, T., Heini, P.F., Clinical measurements of cement injection pressure during vertebroplasty (2005) Spine, 30 (5), pp. E118-E122; Draget, K.I., Skjak-Braek, G., Smidsrod, O., Alginate-based new materials (1997) Int. J. Biol. Macromol., 21 (1-2), pp. 47-55
Keywords: Alginate; alginic acid; article; Biocompatibility; Biocompatible Materials; Capsules; Carboxymethylcellulose; Drug Compounding; Durapatite; Excipients; hydroxyapatite; Hydroxypropylmethylcellulose; Injectability; injection; Injections; instrument sterilization; microsphere; Microspheres; minimally invasive surgery; molecular weight; orthopedic equipment; Polymers; priority journal; Solutions; Vehicles; viscometry

Characterization of two DLC coatings for joint prosthesis: The role of albumin on the tribological behavior - Carapeto, A.P.; Serro, A.P.; Nunes, B.M.F.; Martins, M.C.L.; Todorovic, S.; Duarte, M.T.; André, V.; Colaço, R.; Saramago, B. (Surface and Coatings TechnologySurf. Coat. Technol., 2010)
A commonly used strategy for reduction of wear and friction of the sliding surfaces in prosthetic pairs is the use of hard coatings. DLCs (diamond like carbons) offer a promising solution, because these coatings, already used in other biomedical applications, exhibit a unique combination of chemical inertness, mechanical and tribological properties. In the present work we investigated the role of albumin, the most abundant protein in the periprosthetic fluid, on the tribological behavior of two DLCs with different compositions, against ultra-high molecular weight polyethylene (UHMWPE). The results are compared with those obtained with uncoated stainless steel surfaces. We have characterized the coatings by atomic force microscopy, X-ray diffraction, Raman spectroscopy, ultramicrohardness and wettability measurements. The adsorption of albumin onto the surfaces was investigated by ellipsometry and using a quartz crystal microbalance. Both DLCs adsorb a larger amount of protein than stainless steel. The tribological tests were performed in microtribometer aiming for a deeper understanding of the tribological mechanisms which occur at the submicrometric contact scale. Results showed no significant differences between the tribological behavior of the two coatings. Under the tested conditions, the tribological performance does not improve significantly with the application of the DLCs. Moreover, the presence of albumin on the lubricant leads to higher friction of the polymer against all counterfaces. This effect was attributed to the formation of bridges between the two sliding surfaces by the denaturated protein. The significant differences in the adsorbed amounts of protein onto the stainless steel and the two types of DLCs did not affect considerably the tribological behavior of these materials. © 2010 Elsevier B.V.
Cited By (since 1996): 6Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.surfcoat.2010.04.022Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Química Estrutural, Complexo I, Instituto Superior Técnico, Av. Rovisco Pais, TU Lisbon, 1049-001 Lisboa, Portugal; email: anapaula.serro@ist.utl.ptReferences: Donnet, C., Erdemir, A., (2009), Springer Science & Business Media, New YorkGutensohn, K., Beythien, C., Bau, J., Fenner, T., Grewe, P., Koester, R., Padmanaban, K., Kuehnl, P., (2000) Thromb. Res., 99, p. 577;Cadosch, D., Chan, E., Gautschi, O.P., Simmen, H.-P., Filgueira, L., (2009) J. Orthop. Res., 27, p. 841; Gillespie, W.L., Frampton, C.M.A., Henderson, R.J., Ryan, P.M., (1988) J. Bone Joint Surg. Br., 70 (4), p. 539; Roy, R.K., Lee, K.-R., (2007) J. Biomed. Mater. Res. B Appl. Biomater., 83 B (1), p. 72; Alakoski, E., Tiainen, V.-M., Soininen, A., Konttinen, Y.T., (2008) Open Orthop. J., 2, p. 43; Fisher, J., Firkins, P., Reeves, E.A., Hailey, J.L., Isaac, G.H., (1995) Proc. Inst. Mech. Eng., 209, p. 263; Sheeja, D., Tay, B.K., Lau, S.P., Nung, L.N., (2001) Surf. Coat. Technol., p. 410; Tiainen, V.-M., (2001) Diamond Relat. Mater., 10 (2), p. 153; Oñate, J.I., Comin, M., Braceras, I., Garcia, A., Viviente, J.L., Brizuela, M., Garagorri, N., Alava, J.I., (2001) Surf. Coat. Technol., p. 1056; Shi, B., Ajayi, O.O., Fenske, G., Erdemir, A., Liang, H., (2003) Wear, 255, p. 1015; Lappalainen, R., Selenius, M., Anttila, A., Konttinen, Y.T., Santavirta, S.S., (2003) J. Appl. Biomater., 66 B, p. 410; Sheeja, D., Tay, B.K., Nung, L.N., (2004) Diamond Relat. Mater., 13, p. 184; Xu, T., Pruitt, L., (1999) J. Mater. Sci. Mater. Med., 10, p. 83; Lappalainen, R., Anttila, A., Heinonen, H., (1998) Clin. Orthop., 352, p. 118; Saikko, V., Ahlroos, T., Calonius, O., Keränen, J., (2001) Biomaterials, 22, p. 1507; Sheeja, D., Tay, B.K., Lau, S.P., Nung, L.N., (2001) Surf. Coat. Technol., 146, p. 410; Affatato, S., Frigo, M., Toni, A., (2000) J. Biomed. Mater. Res., 53 (3), p. 221; Scholes, S.C., Unsworth, A., Goldsmit, A.A.J., (2000) Phys. Med. Biol., 45, p. 3721; Ahlroos, T., Saikko, V., (1997) Wear, 211, p. 113; Fedel, M., Motta, A., Maniglio, D., (2009) J. Biomed. Mater. Res., 90 B (1), p. 338; Lousiniana, S., Logothetidis, S., Laskarakisa, A., Gioti, M., (2007) Biomolec. Eng., 24 (1), p. 107; Li, B.G., Kang, Y.Q., Yin, G.F., Zheng, C.Q., (2007) Key Eng. Mater. High-Performance Ceram. IV, p. 1814; Fenske, G.R., (2009) Presented to Chicago Section STLE meeting, , M; Eryilmaz, O.L., Erdemir, A., (2008) Surf. Coat. Technol., 203, p. 750; Gerwin, N., Hops, C., Lucke, A., (2006) Adv. Drug Deliv. Rev., 58 (2), p. 226; Visco, A.M., Torrisi, L., Campo, N., Emanuele, U., Trifiro, A., Trimarchi, M., (2009) J. Biomed. Mater. Res. B Appl. Biomater., 89 B, p. 55; Ferrari, A.C., Robertson, J., (2001) Phys. Rev. B, 64, p. 75414; Ferrari, A.C., Robertson, J., (2000) Phys. Rev. B, 61, p. 14095; Zhou, B., Prorok, B.C., Erdemir, A., Eryilmaz, O., (2007) Diamond Relat. Mater., 16, p. 342; Zhou, B., Prorok, B.C., Erdemir, A., Eryilmaz, O., (2006) Diamond Relat. Mater., 15, p. 2051; Beeman, D., Silverman, J., Lynds, R., Anderson, M.R., (1984) Phys. Rev. B., 30 (2), p. 870; Colaço, R., Serro, A.P., Eryilmaz, O.L., Erdemir, E., (2009) J. Phys. D Appl. Phys., 42, p. 85307; Paul, R., Das, S.N., Dalui, S., Gayen, R.N., Roy, R.K., Bhar, R., Pal, A.K., (2008) J. Phys. D Appl. Phys., 41 (5), p. 55309; Serro, A.P., Fernandes, A.C., Saramago, B., (1997) Colloids Surf. A Physicochem. Eng. Aspects, 125, p. 209; Serro, A.P., Degiampietro, K., Colaço, R., Saramago, B., (2010) Saramago, Adsorption of albumin and sodium hyaluronate on UHMWPE: A QCM-D and AFM study, Colloids and Surfaces B: Biointerfaces, 78, p. 1; de Feijter, J.A., Benjamins, J., Veer, F.A., (1978) Biopolymers, 17, p. 1759; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., (2008) Surf. Int. Anal., 40 (12), p. 1529; Hook, F., Kasemo, B., Nylander, T., Fant, C., Sott, K., Elwing, H., (2001) Anal. Chem., 73 (24), p. 5796; Hook, F., Voros, J., Rodahl, M., Kurrat, R., Boni, P., Ramsden, J.J., Textor, M., Kasemo, B., (2002) Colloids Surf. B Biointerfaces, 24, p. 155; Colaço, R., Gispert, M.P., Serro, A.P., Saramago, B., (2007) Tribol. Lett., 26 (2), p. 119; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., (2006) Wear, 260, p. 149; Serro, A.P., Completo, C., Colaço, R., Dos Santos, F., Lobato da Silva, C., Cabral, J.M.S., Araújo, H., Saramago, B., (2009) Surf. Coat. Technol., 203, p. 3701; Widmer, M.R., Heuberger, M., Vörös, J., Spencer, N.D., (2001) Tribol. Lett., 10, p. 111; Chen, X.M., Jin, Z.M., Fisher, J., (2008) Proc. Inst. Mech. Eng. Part J. Eng. Tribol., 222 (3), p. 513; Kumar, P., Oka, M., Ikeuchi, K., Shimizu, K., Yamamuro, T., Okumura, H., Kotoura, Y., (1991) J. Biomater. Mater. Res., 25, p. 813; Roba, M., Naka, M., Gautier, E., Spencer, N.D., Crockett, R., (2009) Biomaterials, 30, p. 2072; Karuppiah, K.S.K., Sundararajan, S., Xu, Z.-H., Li, X., (2006) Tribol. Lett., 22 (2), p. 181; Yang, C.-B., Fang, H.-W., Liu, H.-L., Chang, C.-H., Hsieh, M.-C., Lee, W.-M., Huang, H.-T., (2006) Chem. Phys. Lett., 431, p. 380; Fang, H.-W., Wang, H.-C., Tsai, T.-H., Tsai, W.-B., Hou, S.-Y., Liu, H.-L., Lee, W.-H., Huang, C.-H., (2008) J. Appl. Polym. Sci., 108, p. 2428; Zappone, B., Rosenberg, K.J., Israelachvili, J., (2007) Tribol. Lett., 26 (3), p. 191; Grill, A., (1997) Surf. Coat. Technol., (1-3), p. 507; Fontaine, J., Belin, M., Le Mogne, T., Grill, A., (2004) Tribol. Int., 37, p. 869; Sanchez-Lopez, J.C., Erdemir, A., Donnet, C., Rojas, T.C., (2003) Surf. Coat. Technol., 163, p. 444; Robertson, J., (2002) Mater. Sci. Eng., 37, p. 129
Keywords: Adsorbed amount; Adsorption; Albumin adsorption; Atomic force microscopy; Atomic spectroscopy; Biomedical applications; Chemical inertness; Corrosion resistant alloys; Diamond like carbon; DLC coatings; Friction; Hard coatings; Joint prostheses; Mechanical and tribological properties; Mechanical properties; Microtribology; Microtribometer; Nonmetallic matrix composites; Oxide minerals; Polyethylenes; Proteins; Quartz; Raman spectroscopy; Scanning electron microscopy; Sliding surface; Stainless steel; Stainless steel surface; Steel corrosion; Surfaces; Tribological behaviors; Tribological mechanism; Tribological performance; Tribological tests; Tribology; UHMW-PE; UHMWPE; Ultramicrohardness; Wear and friction; Wettability measurements; X ray diffraction

Chitosan-based gene delivery vectors targeted to the peripheral nervous system - Oliveira, H.; Pires, L.R.; Fernandez, R.; Martins, M.C.L.; Simões, S.; Pêgo, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
A non-toxic, targeted, simple and efficient system that can specifically transfect peripheral sensorial neurons can pave the way towards the development of new therapeutics for the treatment of peripheral neuropathies. In this study chitosan (CH), a biodegradable polymer, was used as the starting material in the design of a multicomponent vector targeted to the peripheral nervous system (PNS). Polycation-DNA complexes were optimized using imidazole-and thiol-grafted CH (CHimiSH), in order to increase transfection efficiency and allow the formation of ligand conjugated nanocomplexes, respectively. The 50 kDa non-toxic fragment from the tetanus toxin (HC), shown to interact specifically with peripheral neurons and undergo retrograde transport, was grafted to the binary complex via a bi-functional poly(ethylene glycol) (HC-PEG) reactive for the thiol moieties present in the complex surface. The targeting of the developed nanocomplexes was assessed by means of internalization and transfection studies in the ND7/23 (neuronal) vs. NIH 3T3 (fibroblast) cell lines. Targeted transfection was further confirmed in dorsal root ganglion dissociated primary cultures. A versatile, multi-component nanoparticle system that successfully targets and transfects neuronal cell lines, as well as dorsal root ganglia (DRG) primary neuron cultures was obtained for the 1.0 (w/w) HC-PEG/DNA formulation. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32874PubMed ID: 20734332Language of Original Document: EnglishCorrespondence Address: Pêgo, A. P.; INEB, Instituto de Engenharia Biomédica, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; chitosan, 9012-76-4; imidazole, 1467-16-9, 288-32-4; macrogol, 25322-68-3; Cations; Chitosan, 9012-76-4; DNA, 9007-49-2; Polyethylene GlycolsTradenames: Chimarin, medicarb, SwedenManufacturers: medicarb, SwedenReferences: Rodriguez, F.J., Valero-Cabre, A., Navarro, X., Regeneration and functional recovery following peripheral nerve injury (2004) Drug Discov Today, 1, pp. 177-185;Apfel, S.C., Neurotrophic factors in peripheral neuropathies: Therapeutic implications (1999) Brain Pathol, 9, pp. 393-413; Apfel, S.C., Is the therapeutic application of neurotrophic factors dead? (2002) Ann Neurol, 51, pp. 8-11; Glorioso, J.C., Mata, M., Fink, D.J., Therapeutic gene transfer to the nervous system using viral vectors (2003) J Neurovirol, 9, pp. 165-172; Fishman, P.S., Carrigan, D.R., Retrograde transneuronal transfer of the C-fragment of tetanus toxin (1987) Brain Res, 406, pp. 275-279; Evinger, C., Erichsen, J.T., Transsynaptic retrograde transport of fragment C of tetanus toxin demonstrated by immunohistochemical localization (1986) Brain Res, 380, pp. 383-388; Figueiredo, D.M., Hallewell, R.A., Chen, L.L., Fairweather, N.F., Dougan, G., Savitt, J.M., Parks, D.A., Fishman, P.S., Delivery of recombinant tetanus-superoxide dismutase proteins to central nervous system neurons by retrograde axonal transport (1997) Exp Neurol, 145 (2 PART 1), pp. 546-554; Fishman, P.S., Savitt, J.M., Farrand, D.A., Enhanced CNS uptake of systemically administered proteins through conjugation with tetanus C-fragment (1990) J Neurol Sci, 98, pp. 311-325; Coen, L., Osta, R., Maury, M., Brulet, P., Construction of hybrid proteins that migrate retrogradely and transynaptically into the central nervous system (1997) Proc Natl Acad Sci USA, 94, pp. 9400-9405; Knight, A., Carvajal, J., Schneider, H., Coutelle, C., Chamberlain, S., Fairweather, N., Non-viral neuronal gene delivery mediated by the HC fragment of tetanus toxin (1999) Eur J Biochem, 259, pp. 762-769; Oliveira, H., Fernandez, R., Pires, L.R., Simões, S., Martins, M.C.L., Barbosa, M.A., Pêgo, A.P., Targeted gene delivery into peripheral sensorial neurons mediated by self-assembled vectors composed of poly(ethilenimine) and tetanus toxin fragment c (2010) J Control Release, 143, pp. 350-358; Neu, M., Fischer, D., Kissel, T., Recent advances in rational gene transfer vector design based on poly(ethylene imine) and its derivatives (2005) J Gene Med, 7, pp. 992-1009; Tang, G.P., Guo, H.Y., Alexis, F., Wang, X., Zeng, S., Lim, T.M., Ding, J., Wang, S., Low molecular weight polyethylenimines linked by beta-cyclodextrin for gene transfer into the nervous system (2006) J Gene Med, 8, pp. 736-744; Chollet, P., Favrot, M.C., Hurbin, A., Coll, J.L., Side-effects of a systemic injection of linear polyethylenimine-DNA complexes (2002) J Gene Med, 4, pp. 84-91; Shi, C., Zhu, Y., Ran, X., Wang, M., Su, Y., Cheng, T., Therapeutic potential of chitosan and its derivatives in regenerative medicine (2006) J Surg Res, 133, pp. 185-192; Mansouri, S., Lavigne, P., Corsi, K., Benderdour, M., Beaumont, E., Fernandes, J.C., Chitosan-DNA nanoparticles as non-viral vectors in gene therapy: Strategies to improve transfection efficacy (2004) Eur J Pharm Biopharm, 57, pp. 1-8; Moreira, C., Oliveira, H., Pires, L.R., Simoes, S., Barbosa, M.A., Pego, A.P., Improving chitosan-mediated gene transfer by the introduction of intracellular buffering moieties into the chitosan backbone (2009) Acta Biomater, 5, pp. 2995-3006; Verma, A., Stellacci, F., Effect of surface properties on nanoparticle-cell interactions (2010) Small, 6, pp. 12-21; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test As An End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services. US Department of Health and Human Services; MacUlotti, K., Genta, I., Perugini, P., Imam, M., Bernkop-Schnurch, A., Pavanetto, F., Preparation and in vitro evaluation of thiolated chitosan microparticles (2005) J Microencapsul, 22, pp. 459-470; Mao, H., Roy, K., Troung-Le, V.L., Janes, K.A., Lin, K.Y., Wang, Y., August, J.T., Leong, K.W., Chitosan-DNA nanoparticles as gene carriers: Synthesis, characterization and transfection efficiency (2001) J Control Release, 70, pp. 399-421; Innes, N.P.T., Ogden, G.R., A technique for the study of endocytosis in human oral epithelial cells (1999) Arch Oral Biol, 44, pp. 519-523; O'Brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar Blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) Eur J Biochem, 267, pp. 5421-5426; Ellman, G.L., Tissue sulfhydryl groups (1959) Arch Biochem Biophys, 82, pp. 70-77; Lee, D., Zhang, W., Shirley, S.A., Kong, X., Hellermann, G.R., Lockey, R.F., Mohapatra, S.S., Thiolated chitosan/DNA nanocomplexes exhibit enhanced and sustained gene delivery (2007) Pharm Res, 24, pp. 157-167; Loretz, B., Thaler, M., Bernkop-Schnurch, A., Role of sulfhydryl groups in transfection? A case study with chitosan-NAC nanoparticles (2007) Bioconjug Chem, 18, pp. 1028-1035; Deinhardt, K., Berninghausen, O., Willison, H.J., Hopkins, C.R., Schiavo, G., Tetanus toxin is internalized by a sequential clathrin-dependent mechanism initiated within lipid microdomains and independent of epsin 1 (2006) J Cell Biol, 174, pp. 459-471; Williamson, L.C., Neale, E.A., Bafilomycin A1 inhibits the action of tetanus toxin in spinal-cord neurons in cell-culture (1994) J Neurochem, 63, pp. 2342-2345; Bohnert, S., Schiavo, G., Tetanus toxin is transported in a novel neuronal compartment characterized by a specialized pH regulation (2005) J Biol Chem, 280, pp. 42336-42344
Keywords: animal cell; Animals; article; Binary complexes; Biodegradable polymers; Carbohydrate Conformation; Carbohydrate Sequence; Cations; Cell culture; Cell lines; cell population; Cells, Cultured; Chitin; chitosan; Complex surface; DNA; DNA complex; Dorsal root ganglia; Efficient systems; embryo; Ethylene; Ethylene Glycol; Female; Ganglia, Spinal; Gene delivery; gene delivery system; Gene delivery vectors; Gene therapy; Gene transfer; Gene Transfer Techniques; genetic transfection; Genetic Vectors; Grafting (chemical); Humans; imidazole; macrogol; materials testing; Mice; Molecular Sequence Data; Molecular Structure; mouse; Multicomponents; Nanocomplexes; Nanoparticle systems; nanoparticles; nerve cell culture; Neuron culture; Neuronal cell; NIH 3T3 Cells; nonhuman; Nontoxic fragment of tetanus toxin; Peripheral nervous system; Peripheral neuropathy; Polycations; Polyethylene Glycols; Polyethylene oxides; Pregnancy; Primary culture; rat; Rats; Rats, Wistar; spinal ganglion; Starting materials; Targeted; Tetanus toxin; Toxic materials; Transfection; Transfection efficiency

Chitosan/siRNA nanoparticles biofunctionalize nerve implants and enable neurite outgrowth - Mittnacht, U.; Hartmann, H.; Hein, S.; Oliveira, H.; Dong, M.; Pêgo, A.P.; Kjems, J.; Howard, K.A.; Schlosshauer, B. (Nano LettersNano Lett., 2010)
Microstructured 20 μm thick polymer filaments used as nerve implants were loaded with chitosan/siRNA nanoparticles to promote nerve regeneration and ensure local delivery of nanotherapeutics. The stable nanoparticles were rapidly internalized by cells and did not affect cell viability. Target mRNA was successfully reduced by 65-75% and neurite outgrowth was enhanced even in an inhibitory environment. This work, thus, supports the application of nanobiofunctionalized implants as a novel approach for spinal cord and nerve repair. © 2010 American Chemical Society.
Cited By (since 1996): 14Export Date: 21 November 2012Source: Scopusdoi: 10.1021/nl1016909Language of Original Document: EnglishCorrespondence Address: Schlosshauer, B.; NMI Natural and Medical Sciences Institute, University of Tübingen, Markwiesenstrasse 55, 72770 Reutlingen, Germany; email: schlosshauer@nmi.deChemicals/CAS: chitosan, 9012-76-4; Chitosan, 9012-76-4; RNA, Small Interfering; rhoA GTP-Binding Protein, 3.6.5.2References: Terzis, J.K., Skoulis, T.G., Soucacos, P.N., (1995) Int. Angiol., 14, pp. 264-77;Schmidt, C.E., Leach, J.B., (2003) Annu. Rev. Biomed. Eng., 5, pp. 293-347; Stokols, S., Tuszynski, M.H., (2004) Biomaterials, 25 (27), pp. 5839-46; Goraltchouk, A., Scanga, V., Morshead, C.M., Shoichet, M.S., (2006) J. Controlled Release, 110 (2), pp. 400-7; Wu, J., Chiu, D.T., (1999) Ann. Plast. Surg., 43, pp. 661-667; Chen, M.S., Huber, A.B., Van Der Haar, M.E., Frank, M., Schnell, L., Spillmann, A.A., Christ, F., Schwab, M.E., (2000) Nature, 403 (6768), pp. 434-9; Grandpre, T., Nakamura, F., Vartanian, T., Strittmatter, S.M., (2000) Nature, 403 (6768), pp. 439-44; Liu, B.P., Fournier, A., Grandpre, T., Strittmatter, S.M., (2002) Science, 297 (5584), pp. 1190-3; McKerracher, L., David, S., Jackson, D.L., Kottis, V., Dunn, R.J., Braun, P.E., (1994) Neuron, 13 (4), pp. 805-11; Mukhopadhyay, G., Doherty, P., Walsh, F.S., Crocker, P.R., Filbin, M.T., (1994) Neuron, 13 (3), pp. 757-67; Wang, K.C., Koprivica, V., Kim, J.A., Sivasankaran, R., Guo, Y., Neve, R.L., He, Z., (2002) Nature, 417 (6892), pp. 941-4; Mi, S., Lee, X., Shao, Z., Thill, G., Ji, B., Relton, J., Levesque, M., Pepinsky, R.B., (2004) Nat. Neurosci., 7 (3), pp. 221-8; Park, J.B., Yiu, G., Kaneko, S., Wang, J., Chang, J., He, X.L., Garcia, K.C., He, Z., (2005) Neuron, 45 (3), pp. 345-51; Shao, Z., Browning, J.L., Lee, X., Scott, M.L., Shulga-Morskaya, S., Allaire, N., Thill, G., Mi, S., (2005) Neuron, 45 (3), pp. 353-9; Wang, K.C., Kim, J.A., Sivasankaran, R., Segal, R., He, Z., (2002) Nature, 420 (6911), pp. 74-8; Wong, S.T., Henley, J.R., Kanning, K.C., Huang, K.H., Bothwell, M., Poo, M.M., (2002) Nat. Neurosci., 5 (12), pp. 1302-8; Elbashir, S.M., Harborth, J., Lendeckel, W., Yalcin, A., Weber, K., Tuschl, T., (2001) Nature, 411 (6836), pp. 494-8; Higuchi, H., Yamashita, T., Yoshikawa, H., Tohyama, M., (2003) Biochem. Biophys. Res. Commun., 301 (3), pp. 804-9; Fire, A., Xu, S., Montgomery, M.K., Kostas, S.A., Driver, S.E., Mello, C.C., (1998) Nature, 391 (6669), pp. 806-11; Tijsterman, M., Plasterk, R.H., (2004) Cell, 117 (1), pp. 1-3; De Fougerolles, A., Vornlocher, H.P., Maraganore, J., Lieberman, J., (2007) Nat. Rev. Drug Discovery, 6 (6), pp. 443-53; Shrivastava, N., Srivastava, A., (2008) Biotechnol. J., 3 (3), pp. 339-53; Soutschek, J., Akinc, A., Bramlage, B., Charisse, K., Constien, R., Donoghue, M., Elbashir, S., Vornlocher, H.P., (2004) Nature, 432 (7014), pp. 173-8; Takeshita, F., Ochiya, T., (2006) Cancer Sci., 97 (8), pp. 689-96; Bitko, V., Musiyenko, A., Shulyayeva, O., Barik, S., (2005) Nat. Med., 11 (1), pp. 50-5; Fjose, A., Drivenes, O., (2006) Birth Defects Res., C, 78 (2), pp. 150-71; Whitehead, K.A., Langer, R., Anderson, D.G., (2009) Nat. Rev. Drug Discovery, 8 (2), pp. 129-38; Liu, X., Howard, K.A., Dong, M., Andersen, M.O., Rahbek, U.L., Johnsen, M.G., Hansen, O.C., Kjems, J., (2007) Biomaterials, 28 (6), pp. 1280-8; Howard, K.A., Rahbek, U.L., Liu, X., Damgaard, C.K., Glud, S.Z., Andersen, M.O., Hovgaard, M.B., Kjems, J., (2006) Mol. Ther., 14 (4), pp. 476-84; Sell, S.A., McClure, M.J., Barnes, C.P., Knapp, D.C., Walpoth, B.H., Simpson, D.G., Bowlin, G.L., (2006) Biomed. Mater., 1 (2), pp. 72-80; Janes, K.A., Calvo, P., Alonso, M.J., (2001) Adv. Drug Delivery Rev., 47 (1), pp. 83-97; Pouton, C.W., Seymour, L.W., (2001) Adv. Drug Delivery Rev., 46 (1-3), pp. 187-203; Nel, A.E., Madler, L., Velegol, D., Xia, T., Hoek, E.M., Somasundaran, P., Klaessig, F., Thompson, M., (2009) Nat. Mater., 8 (7), pp. 543-57; Ishii, T., Okahata, Y., Sato, T., (2001) Biochim. Biophys. Acta, 1514 (1), pp. 51-64; Huang, M., Fong, C.W., Khor, E., Lim, L.Y., (2005) J. Controlled Release, 106 (3), pp. 391-406; Richardson, S.C., Kolbe, H.V., Duncan, R., (1999) Int. J. Pharm., 178 (2), pp. 231-43; Corsi, K., Chellat, F., Yahia, L., Fernandes, J.C., (2003) Biomaterials, 24 (7), pp. 1255-64; Moghimi, S.M., Symonds, P., Murray, J.C., Hunter, A.C., Debska, G., Szewczyk, A., (2005) Mol. Ther., 11 (6), pp. 990-5; Koping-Hoggard, M., Tubulekas, I., Guan, H., Edwards, K., Nilsson, M., Varum, K.M., Artursson, P., (2001) Gene Ther., 8 (14), pp. 1108-21; Moreira, C., Oliveira, H., Pires, L.R., Simoes, S., Barbosa, M.A., Pego, A.P., (2009) Acta Biomater., 5 (8), pp. 2995-3006; Lietz, M., Dreesmann, L., Hoss, M., Oberhoffner, S., Schlosshauer, B., (2006) Biomaterials, 27 (8), pp. 1425-36; Ribeiro-Resende, V.T., Koenig, B., Nichterwitz, S., Oberhoffner, S., Schlosshauer, B., (2009) Biomaterials, 30 (29), pp. 5251-9; Andersen, M.O., Howard, K.A., Paludan, S.R., Besenbacher, F., Kjems, J., (2008) Biomaterials, 29 (4), pp. 506-12; Anchordoquy, T.J., Allison, S.D., Molina, M.C., Girouard, L.G., Carson, T.K., (2001) Drug Discovery Today, 6 (9), pp. 463-470; Atala, A., Bauer, S.B., Soker, S., Yoo, J.J., Retik, A.B., (2006) Lancet, 367 (9518), pp. 1241-6; Lin, C.Y., Schek, R.M., Mistry, A.S., Shi, X., Mikos, A.G., Krebsbach, P.H., Hollister, S.J., (2005) Tissue Eng., 11 (9-10), pp. 1589-98; Suggate, E.L., Ahmed, Z., Read, M.L., Eaton-Charnock, K., Douglas, M.R., Gonzalez, A.M., Berry, M., Logan, A., (2009) Mol. Cell Neurosci., 40 (4), pp. 451-62; Ahmed, Z., Dent, R.G., Suggate, E.L., Barrett, L.B., Seabright, R.J., Berry, M., Logan, A., (2005) Mol. Cell Neurosci., 28 (3), pp. 509-23; Fournier, A.E., Takizawa, B.T., Strittmatter, S.M., (2003) J. Neurosci., 23 (4), pp. 1416-23
Keywords: animal; Animals; article; Cell Line; cell viability; chemistry; Chitin; chitosan; cytology; Drug delivery; genetic transfection; genetics; Local delivery; metabolism; Microstructured; nanobiofunctionalized implants; nanoparticle; nanoparticles; nerve cell; nerve regeneration; Nerve repair; neurite; Neurite outgrowth; Neurites; Neurons; Polymer filaments; Prostheses and Implants; prostheses and orthoses; rhoA GTP-Binding Protein; RhoA guanine nucleotide binding protein; RNA; RNA, Small Interfering; siRNA; small interfering RNA; Spinal cords; Transfection; ultrastructure

Comparison of a computer system evaluation of intrapartum cardiotocographic events and a consensus of clinicians. - Costa, M.A.; Ayres-de-Campos, D.; Machado, A.P.; Santos, C.C.; Bernardes, J. (Journal of perinatal medicineJ Perinat Med, 2010)
AIMS: To compare between computer analysis of intrapartum cardiotocography (CTG) features by the Omniview-SisPorto 3.5 and a consensus of clinicians. METHODS: Agreement study using 50 consecutively acquired tracings (206 h of signals) with >60 min duration, <10% signal loss and recorded in labor at term by internal fetal heart rate (FHR) monitoring. Tracings were divided into 10-min segments and independently analyzed by three experienced clinicians, in order to estimate the FHR baseline and identify periodic events. A consensus was reached using a three round Delphi procedure. Results were compared with the analysis provided by the Omniview-SisPorto 3.5 system. RESULTS: For baseline estimation, agreement between the computer and the consensus was high [intraclass correlation coefficient (ICC)=0.85; 95% confidence interval (CI) 0.46-0.93], with a mean difference of 3.7 bpm (limits of agreement -4.4-11.9 bpm), and 99% of differences under 15 bpm. A concordant identification was observed in 71% of accelerations (95% CI: 69%-73%), 68% of decelerations (95% CI: 66%-70%), and 87% of uterine contractions (95% CI: 85%-89%). CONCLUSIONS: A high agreement was observed between the Omniview-SisPorto 3.5 and a consensus of clinicians in evaluation of intrapartum CTG baseline, accelerations, decelerations and uterine contractions.
Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1515/JPM.2010.030PubMed ID: 20121542Language of Original Document: EnglishCorrespondence Address: Costa, M.A.email: cosantonia@gmail.com
Keywords: algorithm; Algorithms; article; Cardiotocography; comparative study; computer assisted diagnosis; Diagnosis, Computer-Assisted; Female; Fetal Heart; Fetal monitoring; fetus heart; fetus monitoring; human; Humans; instrumentation; methodology; physician; Physicians; physiology; Pregnancy

De novo expression of CD44 variants in sporadic and hereditary gastric cancer - Da Cunha, C.B.; Oliveira, C.; Wen, X.; Gomes, B.; Sousa, S.; Suriano, G.; Grellier, M.; Huntsman, D.G.; Carneiro, F.; Granja, P.L.; Seruca, R. (Laboratory InvestigationLab. Invest., 2010)
CD44 is the major ubiquitously expressed cell surface receptor for hyaluronate. The CD44 gene encodes several protein isoforms due to extensive alternative splicing and post-translational modifications. Some of these CD44 variable isoforms have been foreseen as key players in malignant transformation and their expression is highly restricted and highly specific, unlike the canonical CD44 standard isoform. In this study, we aimed at dissecting the mRNA splicing pattern of CD44 in normal stomach and gastric cancer (GC) cell lines (n9) using cloning and quantitative mRNA amplification assays. Moreover, we assessed the RNA levels and protein expression pattern of relevant splicing forms in distinct premalignant and malignant gastric lesions (sporadic (n43) and hereditary (n3) forms) using real-time RT-PCR and immunohistochemistry. We also explored the association of CD44 and E-cadherin expression by immunohistochemistry, as E-cadherin has a pivotal functional role in GC. We established the pattern of CD44 variant forms in normal stomach and gastric malignancy. We observed that although exon v6-containing isoforms were rarely expressed in normal gastric mucosa, they became increasingly expressed both in gastric premalignant (hyperplastic polyps, complete and incomplete intestinal metaplasia, low- and high-grade dysplasia) and malignant lesions (cell lines derived from GCs, primary sporadic GCs and hereditary diffuse GCs (HDGCs)). Moreover, we verified that whenever E-cadherin expression was absent, exon v6-containing CD44 isoforms were overexpressed. The lack of expression of CD44 isoforms containing exon v6 in the surface and foveolar epithelia of normal stomach and, its de novo expression in premalignant, as well as in sporadic and hereditary malignant lesions of the stomach, pinpoint CD44 v6-containg isoforms as potential biomarkers for early transformation of the gastric mucosa. Further, our results raise the hypothesis of using CD44v6 as a marker of early invasive intramucosal carcinoma in HDGC CDH1 mutation carriers that lack CDH1 expression in their tumors. © 2010 USCAP, Inc All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: LAINAdoi: 10.1038/labinvest.2010.155PubMed ID: 20856229Language of Original Document: EnglishCorrespondence Address: Da Cunha, C. B.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3; Antigens, CD44; CD44 protein, human; CD44v6 antigen; Cadherins; RNA, MessengerReferences: Aruffo, A., Stamenkovic, I., Melnick, M., CD44 is the principal cell surface receptor for hyaluronate (1990) Cell, 61, pp. 1303-1313;Screaton, G.R., Bell, M.V., Jackson, D.G., Genomic structure of DNA encoding the lymphocyte homing receptor CD44 reveals at least 12 alternatively spliced exons (1992) Proc Natl Acad Sci USA, 89, pp. 12160-12164; Ponta, H., Wainwright, D., Herrlich, P., Molecules in focus the CD44 protein family (1998) Int J Biochem Cell Biol, 30, pp. 299-305; Rudzki, Z., Jothy, S., CD44 and the adhesion of neoplastic cells (1997) Mol Pathol, 50, pp. 57-71; Shtivelman, E., Bishop, J.M., Expression of CD44 is repressed in neuroblastoma cells (1991) Mol Cell Biol, 11, pp. 5446-5453; De Marzo, A.M., Bradshaw, C., Sauvageot, J., CD44 and CD44v6 downregulation in clinical prostatic carcinoma: Relation to Gleason grade and cytoarchitecture (1998) Prostate, 34, pp. 162-168; Joensuu, H., Klemi, P.J., Toikkanen, S., Glycoprotein CD44 expression and its association with survival in breast cancer (1993) Am J Pathol, 143, pp. 867-874; Friedrichs, K., Kugler, G., Franke, F., CD44 isoforms in prognosis of breast cancer (1995) Lancet, 345, p. 1237; Kaufmann, M., Heider, K.H., Sinn, H.P., CD44 variant exon epitopes in primary breast cancer and length of survival (1995) Lancet, 345, pp. 615-619; Mulder, J.W., Kruyt, P.M., Sewnath, M., Colorectal cancer prognosis and expression of exon-v6-containing CD44 proteins (1994) Lancet, 344, pp. 1470-1472; Wielenga, V.J., Heider, K.H., Offerhaus, G.J., Expression of CD44 variant proteins in human colorectal cancer is related to tumor progression (1993) Cancer Res, 53, pp. 4754-4756; Terpe, H.J., Koopmann, R., Imhof, B.A., Expression of integrins and CD44 isoforms in non-Hodgkin's lymphomas: CD44 variant isoforms are preferentially expressed in high-grade malignant lymphomas (1994) J Pathol, 174, pp. 89-100; Takaishi, S., Okumura, T., Tu, S., Identification of gastric cancer stem cells using the cell surface marker CD44 (2009) Stem Cells, 27, pp. 1006-1020; Heider, K.-H., Dammrich, J., Skroch-Angel, P., Differential EXpression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Mayer, B., Jauch, K.W., Gunthert, U., De-novo expression of CD44 and survival in gastric cancer (1993) Lancet, 342, pp. 1019-1022; Muller, W., Schneiders, A., Heider, K.H., Expression and prognostic value of the CD44 splicing variants v5 and v6 in gastric cancer (1997) J Pathol, 183, pp. 222-227; Mirecka, J., Marx, D., Schauer, A., Immunohistochemical localization of CD44 variants 5 and 6 in human gastric mucosa and gastric cancer (1995) Anticancer Res, 15, pp. 1459-1465; Heider, K.H., Dammrich, J., Skroch-Angel, P., Differential expression of CD44 splice variants in intestinal-and diffuse-type human gastric carcinomas and normal gastric mucosa (1993) Cancer Res, 53, pp. 4197-4203; Hong, R.L., Lee, W.J., Shun, C.T., Expression of CD44 and its clinical implication in diffuse-type and intestinal-type gastric adenocarcinomas (1995) Oncology, 52, pp. 334-339; Ghaffarzadehgan, K., Jafarzadeh, M., Raziee, H.R., Expression of cell adhesion molecule CD44 in gastric adenocarcinoma and its prognostic importance (2008) World J Gastroenterol, 14, pp. 6376-6381; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Suriano, G., Mulholland, D., De Wever, O., The intracellular E-cadherin germline mutation V832M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Suriano, G., Oliveira, C., Ferreira, P., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum Mol Genet, 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., E-cadherin germline missense mutations and cell phenotype: Evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum Mol Genet, 12, pp. 3007-3016; Oliveira, C., Bordin, M.C., Grehan, N., Screening E-cadherin in gastric cancer families reveals germline mutations only in hereditary diffuse gastric cancer kindred (2002) Hum Mutat, 19, pp. 510-517; MacHado, J.C., Oliveira, C., Carvalho, R., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Huntsman, D.G., Carneiro, F., Lewis, F.R., Early gastric cancer in young, asymptomatic carriers of germ-line E-cadherin mutations (2001) N Engl J Med, 344, pp. 1904-1909; Carneiro, F., MacHado, J.C., Seruca, R., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., E-cadherin mutations and cell motility: A genotype-phenotype correlation (2009) Exp Cell Res, 315, pp. 1393-1402; Oliveira, C., Senz, J., Kaurah, P., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum Mol Genet, 18, pp. 1545-1555; Oliveira, C., Sousa, S., Pinheiro, H., Quantification of epigenetic and genetic second hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Lynch, H.T., Grady, W., Suriano, G., Gastric cancer: New genetic developments (2005) J Surg Oncol, 90, pp. 114-133. , discussion 133; Lauren, P., The two histological main types of gastric carcinoma: Diffuse and so-called intestinal-type carcinoma. An attempt at a histo-clinical classification (1965) Acta Pathol Microbiol Scand, 64, pp. 31-49; Filipe, M.I., Jass, J.R., Intestinal metaplasia subtypes and cancer risk (1986) Gastric Carcinoma, pp. 87-115. , Filipe MI, Jass JR (eds). Churchill Livingstone, London; Sato, S., Yokozaki, H., Yasui, W., Silencing of the CD44 gene by CpG methylation in a human gastric carcinoma cell line (1999) Jpn J Cancer Res, 90, pp. 485-489; Guilford, P.H.J., Harraway, J., McLeod, M., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 26, p. 6674; Günthert, U., Hofmann, M., Rudy, W., A new variant of glycoprotein CD44 confers metastatic potential to rat carcinoma cells (1991) Cell, 65, pp. 13-24; Vr, O., Chen, L., Sleeman, J.P., CD44 is required for two consecutive steps in HGF/c-Met signaling (2002) Genes Dev, 16, pp. 3074-3086; Spk, D., Stefan, M., Wels, C., HGF-Promoted Motility in Primary Melanocytes Depends on CD44v6 Regulated via NF-kappa B, Egr-1, and C/EBP-beta (2010) J Investig Dermatol, 130, pp. 1893-1903; Mielgo, A., Van Driel, M., Bloem, A., A novel antiapoptotic mechanism based on interference of Fas signaling by CD44 variant isoforms (2006) Cell Death Differ, 13, pp. 465-477; Marhaba, R., Bourouba, M., Zoller, M., CD44v6 promotes proliferation by persisting activation of MAP kinases (2005) Cell Signal, 17, pp. 961-973; Bates, R.C., Edwards, N.S., Burns, G.F., A CD44 survival pathway triggers chemoresistance via lyn kinase and phosphoinositide 3-kinase/Akt in colon carcinoma cells (2001) Cancer Res, 61, pp. 5275-5283; Carvalho, R., Milne, A.N., Polak, M., A novel region of amplification at 11p12-13 in gastric cancer, revealed by representational difference analysis, is associated with overexpression of CD44v6, especially in early-onset gastric carcinomas (2006) Genes Chromosomes Cancer, 45, pp. 967-975; Heider, K.H., Hofmann, M., Hors, E., A human homologue of the rat metastasis-associated variant of CD44 is expressed in colorectal carcinomas and adenomatous polyps (1993) J Cell Biol, 120, pp. 227-233; Gulmann, C., Grace, A., Leader, M., CD44v6: A potential marker of malignant transformation in intestinal metaplasia of the stomach? An immunohistochemical study using tissue microarrays (2003) Eur J Gastroenterol Hepatol, 15, pp. 981-986; Wimmel, A., Kogan, E., Ramaswamy, A., Variant expression of CD44 in preneoplastic lesions of the lung (2001) Cancer, 92, pp. 1231-1236; Afify, A.M., Craig, S., Paulino, A.F., Expression of hyaluronic acid and its receptors, CD44s and CD44v6, in normal, hyperplastic, and neoplastic endometrium (2005) Ann Diagn Pathol, 9, pp. 312-318; Soon Cheol, H., Jae Yun, S., Jae Kwan, L., Significance of CD44v6 expression in gynecologic malignancies (2006) J Obstet Gynaecol Res, 32, pp. 379-386; Afify, A., Ma, M., Braggin, J., Expression of CD44s, CD44v6, and hyaluronan across the spectrum of normal-hyperplasia-carcinoma in breast (2008) Appl Immunohistochem Mol Morphol, 16, pp. 121-127; Judd, L.M., Andriga, A., Rubio, C.A., Gastric achlorhydria in H/K-ATPase-deficient (Atp4a(-/-)) mice causes severe hyperplasia, muco-cystic metaplasia and upregulation of growth factors (2005) J Gastroenterol Hepatol, 20, pp. 1266-1278; Liu, Y.J., Yan, P.S., Li, J., Expression and significance of CD44 s, CD44v6, and nm23 mRNA in human cancer (2005) World J Gastroenterol, 11, pp. 6601-6606; Polkowski, W.P., Skomra, D.G., Mielko, J., E-cadherin expression as predictive marker of proximal resection line involvement for advanced carcinoma of the gastric cardia (2004) E J Surg Oncol, 30, pp. 1084-1092; Seiter, S.A.R., Reber, S., Komitowski, D., Prevention of tumor metastasis formation by anti-variant CD44 (1993) J Experiment Med, 177, pp. 443-455; Reeder, J.A., Gotley, D.C., Walsh, M.D., Expression of ANTisense CD44 variant 6 inhibits colorectal tumor metastasis and tumor growth in a wound environment (1998) Cancer Res, 58, pp. 3719-3726; Nishii, T., Yashiro, M., Shinto, O., Cancer stem cell-like SP cells have a high adhesion ability to the peritoneum in gastric carcinoma (2009) Cancer Sci, 100, pp. 1397-1402; Carneiro, F., Huntsman, D.G., Smyrk, T.C., Model of the early development of diffuse gastric cancer in E-cadherin mutation carriers and its implications for patient screening (2004) J Pathol, 203, pp. 681-687; Pdp, P., Guilford, P., Caldas, C., The International Gastric Cancer Linkage C. Incidence of gastric cancer and breast cancer in CDH1 (E-cadherin) mutation carriers from hereditary diffuse gastric cancer families (2001) Gastroenterology, 121, pp. 1348-1353; Humar, B., Fukuzawa, R., Blair, V., Destabilized adhesion in the gastric proliferative zone and c-Src kinase activation mark the development of early diffuse gastric cancer (2007) Cancer Res, 67, pp. 2480-2489; Ferrari, M., Cancer nanotechnology: Opportunities and challenges (2005) Nat Rev Cancer, 5, pp. 161-171; Yww, W., Chen, Y., Huang, K., The investigation of polymer-siRNA nanoparticle for gene therapy of gastric cancer in vitro (2010) Int J Nanomed, 5, pp. 129-136
Keywords: Alternative Splicing; Antigens, CD44; article; Cadherins; CD44; CD44v6; CD44v6 antigen; CD44v7 antigen; Cell Line, Tumor; clinical article; controlled study; E-cadherin; familial cancer; Gastric Mucosa; Germ-Line Mutation; HDGC; Hermes antigen; human; human tissue; Humans; immunohistochemistry; intestine metaplasia; messenger RNA; Neoplasm Metastasis; priority journal; protein expression; real time polymerase chain reaction; reverse transcription polymerase chain reaction; RNA splicing; RNA, Messenger; splicing; sporadic GC; stomach; stomach cancer; stomach mucosa; Stomach Neoplasms; stomach polyp; tumor marker; unclassified drug; uvomorulin

Dynamic cell-cell interactions between cord blood haematopoietic progenitors and the cellular niche are essential for the expansion of CD34 +, CD34 +CD38 - Da Silva, C.L.; Gonçalves, R.; Dos Santos, F.; Andrade, P.Z.; Almeida-Porada, G.; Cabral, J.M.S. (Journal of Tissue Engineering and Regenerative MedicineJ. Tissue Eng. Regenerative Med., 2010)
Most clinical applications of haematopoietic stem/progenitor cells (HSCs) would benefit from their ex vivo expansion to obtain a therapeutically significant amount of cells from the available donor samples. We studied the impact of cellular interactions between umbilical cord blood (UCB) haematopoietic cells and bone marrow (BM)-derived mesenchymal stem cells (MSCs) on the ex vivo expansion and differentiative potential of UCB CD34 +-enriched cells. UCB cells were cultured: (a) directly in contact with BM MSC-derived stromal layers (contact); (b) separated by a microporous membrane (non-contact); or (c) without stroma (no stroma). Highly dynamic culture events occurred in HSC-MSC co-cultures, involving cell-cell interactions, which preceded HSC expansion. Throughout the time in culture [18 days], total cell expansion was significantly higher in contact (fold increase of 280 ± 37 at day 18) compared to non-contact (85 ± 25). No significant cell expansion was observed in stroma-free cultures. CD34 + cell expansion was also clearly favoured by direct contact with BM MSCs (35 ± 5- and 7 ± 3-fold increases at day 18 for contact and non-contact, respectively). Moreover, a higher percentage of CD34 +CD38
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1002/term.226PubMed ID: 19937912Language of Original Document: EnglishCorrespondence Address: Da Silva, C. L.; IBB-Institute for Biotechnology and Bioengineering, Centre for Biological and Chemical Engineering, Instituto Superior Técnico, Avenida Rovisco Pais, 1049-001 Lisbon, Portugal; email: claudialobato@ist.utl.ptChemicals/CAS: Antigens, CD34; Antigens, CD38, 3.2.2.5; Antigens, CD7; SuspensionsReferences: Alakel, N., Jing, D., Muller, K., Direct contact with mesenchymal stromal cells affects migratory behavior and gene expression profile of CD133 + hematopoietic stem cells during ex vivo expansion (2009) Exp Hematol, 37 (4), pp. 504-513;Almeida-Porada, G., Brown, R.L., MacKintosh, F.R., Evaluation of serum-free culture conditions able to support the ex vivo expansion and engraftment of human hematopoietic stem cells in the human-to-sheep xenograft model (2000) J Hematother Stem Cell Res, 9 (5), pp. 683-693; Ando, K., Nakamura, Y., Chargui, J., Extensive generation of human cord blood CD34 + stem cells from Lin -CD34 - cells in a long-term in vitro system (2000) Exp Hematol, 28 (6), pp. 690-699; Bernstein, I.D., Boyd, R.L., van den Brink, M.R., Clinical strategies to enhance posttransplant immune reconstitution (2008) Biol Blood Marrow Transpl, 14 (1 and SUPPL. 1), pp. 94-99; Bilko, N.M., Votyakova, I.A., Vasylovska, S.V., Characterization of the interactions between stromal and haematopoietic progenitor cells in expansion cell culture models (2005) Cell Biol Int, 29 (1), pp. 83-86; Breems, D.A., Blokland, E.A., Siebel, K.E., Stroma contact prevents loss of hematopoietic stem cell quality during ex vivo expansion of CD34 + mobilized peripheral blood stem cells (1998) Blood, 91 (1), pp. 111-117; Cheng, X., Macvittie, T., Meisenberg, B., Human brain endothelial cells (HUBEC) promote SCID repopulating cell expansion through direct contact (2007) Growth Factors, 25 (3), pp. 141-150; Corre, J., Planat-Benard, V., Corberand, J., Human bone marrow adipocytes support complete myeloid and lymphoid differentiation from human CD34 + cells (2004) Br J Haematol, 127 (3), pp. 344-347; da Silva, C.L., Goncalves, R., Crapnell, K.B., A human stromal-based serum-free culture system supports the ex vivo expansion/maintenance of bone marrow and cord blood hematopoietic stem/progenitor cells (2005) Exp Hematol, 33 (7), pp. 828-835; da Silva, C.L., Goncalves, R., Porada, C.D., Differences amid bone marrow and cord blood hematopoietic stem/progenitor cell division kinetics (2009) J Cell Physiol, , DOI: 10.1002/jcp.21736; de Lima, M., Shpall, E., Strategies for widening the use of cord blood in hematopoietic stem cell transplantation (2006) Haematologica, 91 (5), pp. 584-587; Foguenne, J., Di Stefano, I., Giet, O., Ex vivo expansion of hematopoietic progenitor cells is associated with downregulation of α4 integrin- and CXCR4-mediated engraftment in NOD/SCID β2-microglobulin-null mice (2009) Haematologica, 94 (2), pp. 185-194; Freund, D., Bauer, N., Boxberger, S., Polarization of human hematopoietic progenitors during contact with multipotent mesenchymal stromal cells: Effects on proliferation and clonogenicity (2006) Stem Cells Dev, 15 (6), pp. 815-829; Frias, A.M., Porada, C.D., Crapnell, K.B., Generation of functional natural killer and dendritic cells in a human stromal-based serum-free culture system designed for cord blood expansion (2008) Exp Hematol, 36 (1), pp. 61-68; Goncalves, R., Lobato da Silva, C., Cabral, J.M.S., A Stro-1 + human universal stromal feeder layer to expand/maintain human bone marrow hematopoietic stem/progenitor cells in a serum-free culture system (2006) Exp Hematol, 34 (10), pp. 1353-1359; Gordon, M.Y.M.S., Davidson, R.J., Grand, F.H., Contact-mediated inhibition of human hematopoietic progenitor cell proliferationmay be conferred by stem cell antigen, CD34 (2000) Hematol J, 1, pp. 77-86; Hao, Q.L., Zhu, J., Price, M.A., Identification of a novel, human multilymphoid progenitor in cord blood (2001) Blood, 97 (12), pp. 3683-3690; Haylock, D.N., Nilsson, S.K., Osteopontin: A bridge between bone and blood (2006) Br J Haematol, 134 (5), pp. 467-474; Hidalgo, A., Robledo, M.M., Teixido, J., CD44-mediated hematopoietic progenitor cell adhesion and its complex role in myelopoiesis (2002) J Hematother Stem Cell Res, 11 (3), pp. 539-547; Hofmeister, C.C., Zhang, J., Knight, K.L., Ex vivo expansion of umbilical cord blood stem cells for transplantation: Growing knowledge from the hematopoietic niche (2007) Bone Marrow Transpl, 39 (1), pp. 11-23; Jones, P., May, G., Healy, L., Stromal expression of Jagged 1 promotes colony formation by fetal hematopoietic progenitor cells (1998) Blood, 92 (5), pp. 1505-1511; Katayama, Y., Frenette, P.S., Galactocerebrosides are required postnatally for stromal-dependent bone marrow lymphopoiesis (2003) Immunity, 18 (6), pp. 789-800; Kawada, H., Ando, K., Tsuji, T., Rapid ex vivo expansion of human umbilical cord hematopoietic progenitors using a novel culture system (1999) Exp Hematol, 27 (5), pp. 904-915; Kilroy, G.E., Foster, S.J., Wu, X., Cytokine profile of human adipose-derived stem cells: Expression of angiogenic, hematopoietic, and pro-inflammatory factors (2007) J Cell Physiol, 212 (3), pp. 702-709; Kim, J.A., Kang, Y.J., Park, G., Identification of a stromamediated Wnt/β-catenin signal promoting self-renewal of hematopoietic stem cells in the stem cell niche (2009) Stem Cells, 27 (6), pp. 1318-1329; Koller, M.R., Oxender, M., Jensen, T.C., Direct contact between CD34 +lin - cells and stroma induces a soluble activity that specifically increases primitive hematopoietic cell production (1999) Exp Hematol, 27 (4), pp. 734-741; Lewis, I.D., Almeida-Porada, G., Du, J., Umbilical cord blood cells capable of engrafting in primary, secondary, and tertiary xenogeneic hosts are preserved after ex vivo culture in a noncontact system (2001) Blood, 97 (11), pp. 3441-3449; Li, N., Feugier, P., Serrurrier, B., Human mesenchymal stem cells improve ex vivo expansion of adult human CD34 + peripheral blood progenitor cells and decrease their allostimulatory capacity (2007) Exp Hematol, 35 (3), pp. 507-515; Li, Y.P., Paczesny, S., Lauret, E., Human mesenchymal stem cells license adult CD34 + hemopoietic progenitor cells to differentiate into regulatory dendritic cells through activation of the Notch pathway (2008) J Immunol, 180 (3), pp. 1598-1608; Loeuillet, C., Bernard, G., Remy-Martin, J., Distinct hematopoietic support by two human stromal cell lines (2001) Exp Hematol, 29 (6), pp. 736-745; Mayani, H., Lansdorp, P.M., Biology of human umbilical cord blood-derived hematopoietic stem/progenitor cells (1998) Stem Cells, 16 (3), pp. 153-165; McKenzie, J.L., Gan, O.I., Doedens, M., Reversible cell surface expression of CD38 on CD34-positive human hematopoietic repopulating cells (2007) Exp Hematol, 35 (9), pp. 1429-1436; Moore, K.A., Lemischka, I.R., Stem cells and their niches (2006) Science, 311 (5769), pp. 1880-1885; Nolta, J.A., Smogorzewska, E.M., Kohn, D.B., Analysis of optimal conditions for retroviral-mediated transduction of primitive human hematopoietic cells (1995) Blood, 86 (1), pp. 101-110; Oostendorp, R.A., Robin, C., Steinhoff, C., Long-term maintenance of hematopoietic stem cells does not require contact with embryo-derived stromal cells in cocultures (2005) Stem Cells, 23 (6), pp. 842-851; Oritani, K., Wu, X., Medina, K., Antibody ligation of CD9 modifies production of myeloid cells in long-term cultures (1996) Blood, 87 (6), pp. 2252-2261; Sadlon, T.J., Lewis, I.D., D'Andrea, R.J., BMP4: Its role in development of the hematopoietic system and potential as a hematopoietic growth factor (2004) Stem Cells, 22 (4), pp. 457-474; Shih, C.C., Hu, M.C.T., Hu, J., Long-term ex vivo maintenance and expansion of transplantable human hematopoietic stem cells (1999) Blood, 94 (5), pp. 1623-1636; Shpall, E.J., Quinones, R., Giller, R., Transplantation of ex vivo expanded cord blood (2002) Biol Blood Marrow Transpl, 8 (7), pp. 368-376; Suzuki, T., Yokoyama, Y., Kumano, K., Highly efficient ex vivo expansion of human hematopoietic stem cells using Δ1-Fc chimeric protein (2006) Stem Cells, 24 (11), pp. 2456-2465; Verfaillie, C.M., Direct contact between human primitive hematopoietic progenitors and bone marrow stroma is not required for long-term in vitro hematopoiesis (1992) Blood, 79 (11), pp. 2821-2826; Wagner, W., Wein, F., Roderburg, C., Adhesion of hematopoietic progenitor cells to human mesenchymal stem cells as a model for cell-cell interaction (2007) Exp Hematol, 35 (2), pp. 314-325; Yin, T., Li, L., The stem cell niches in bone (2006) J Clin Invest, 116 (5), pp. 1195-1201; Zhang, C.C., Kaba, M., Iizuka, S., Angiopoietin-like 5 and IGFBP2 stimulate ex vivo expansion of human cord blood hematopoietic stem cells as assayed by NOD/SCID transplantation (2008) Blood, 111 (7), pp. 3415-3423; Zhang, Y., Chai, C., Jiang, X.S., Co-culture of umbilical cord blood CD34 + cells with human mesenchymal stem cells (2006) Tissue Eng, 12 (8), pp. 2161-2170
Keywords: Antigens, CD34; Antigens, CD38; Antigens, CD7; article; Bone marrow microenvironment; CD34 antigen; CD38 antigen; CD7 antigen; cell adhesion; Cell Communication; cell contact; Cell culture; cell differentiation; cell interaction; cell proliferation; Cells, Cultured; cellular distribution; clonogenic assay; coculture; Coculture Techniques; Colony-Forming Units Assay; controlled study; Ex vivo expansion; ex vivo study; Fetal Blood; flow cytometry; Haematopoietic stem/progenitor cells; hematopoietic stem cell; Hematopoietic Stem Cells; human; human cell; Humans; Lymphocytes; lymphoid cell; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Electron, Scanning; phenotype; priority journal; Scanning electron microscopy; somatic gene therapy; stem cell expansion; Stem Cell Niche; stroma cell; Suspensions; umbilical cord blood

Early spreading and propagation of human bone marrow stem cells on isotropic and anisotropic topographies of silica thin films produced via microstamping - Pelaez-Vargas, A.; Gallego-Perez, D.; Ferrell, N.; Fernandes, M.H.; Hansford, D.; Monteiro, F.J. (Microscopy and MicroanalysisMicrosc. Microanal., 2010)
While there has been rapid development of microfabrication techniques to produce high-resolution surface modifications on a variety of materials in the last decade, there is still a strong need to produce novel alternatives to induce guided tissue regeneration on dental implants. High-resolution microscopy provides qualitative and quantitative techniques to study cellular guidance in the first stages of cell-material interactions. The purposes of this work were (1) to produce and characterize the surface topography of isotropic and anisotropic microfabricated silica thin films obtained by sol-gel processing, and (2) to compare the in vitro biological behavior of human bone marrow stem cells on these surfaces at early stages of adhesion and propagation. The results confirmed that a microstamping technique can be used to produce isotropic and anisotropic micropatterned silica coatings. Atomic force microscopy analysis was an adequate methodology to study in the same specimen the sintering derived contraction of the microfabricated coatings, using images obtained before and after thermal cycle. Hard micropatterned coatings induced a modulation in the early and late adhesion stages of cell-material and cell-cell interactions in a geometry-dependent manner (i.e., isotropic versus anisotropic), as it was clearly determined, using scanning electron and fluorescence microscopies. © Microscopy Society of America 2010.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: MIMIFdoi: 10.1017/S1431927610094158PubMed ID: 20964878Language of Original Document: EnglishCorrespondence Address: Pelaez-Vargas, A.; INEB - Instituto de Engenharia Biomédica, Faculdade de Engenharia, Departamento de Engenharia Metalrgica e Materiais, Porto, Portugal; email: alejopv@ineb.up.ptChemicals/CAS: silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; Silicon Dioxide, 7631-86-9References: Albrektsson, T., Sennerby, L., Wennerberg, A., State of the art of oral implants (2000) Periodontology, 47, pp. 15-26;Albrektsson, T., Wennerberg, A., Oral implant surfaces: Part 1-Review focusing on topographic and chemical properties of different surfaces and in vivo responses to them (2004) Int J Prosthodont, 17 (5), pp. 536-543; Batista, L.H., Junior, J.G., Silva, M.F., Tonholo, J., Atomic force microscopy of removal of dentin smear layers (2007) Microsc Microanal, 13 (4), pp. 245-250; Baudino, T.A., McFadden, A., Fix, C., Hastings, J., Price, R., Borg, T.K., Cell patterning: Interaction of cardiac myocytes and fibroblasts in three-dimensional culture (2008) MicroscMicroanal, 14 (2), pp. 117-125; Bohil, A.B., Robertson, B.W., Cheney, R.E., Myosin-X is a molecular motor that functions in filopodia formation (2006) Proc Natl Acad Sci USA, 103 (33), pp. 12411-12416; Brunette, D.M., Kenner, G.S., Gould, T.R., Grooved titanium surfaces orient growth and migration of cells from human gingival explants (1983) J Dent Res, 62 (10), pp. 1045-1048; Curtis, A., Wilkinson, C., Topographical control of cells (1997) Biomaterials, 18 (24), pp. 1573-1583; Curtis, A.S., Cell reactions with biomaterials: The microscopies (2001) Eur Cell Mater, 1, pp. 59-65; Dalby, M.J., Riehle, M.O., Johnstone, H., Affrossman, S., Curtis, A.S., Investigating the limits of filopodial sensing: A brief report using SEM to image the interaction between 10 nm high nano-topography and fibroblast filopodia (2004) Cell Biol Int, 28 (3), pp. 229-236; Durán, A., Conde, A., Coedo, A.G., Dorado, T., García, C., Ceré, S., Sol-gel coatings for protection and bioactiva- tion of metals used in orthopaedic devices (2004) J Mater Chem, 14 (14), pp. 2282-2290; Falconnet, D., Csucs, G., Grandin, H.M., Textor, M., Surface engineering approaches to micropattern surfaces for cell-based assays (2006) Biomaterials, 27 (16), pp. 3044-3063; Gallardo, J., Galliano, P., Durán, A., Thermal evolution of hybrid sol-gel silica coatings: A structural analysis (2000) J Sol-Gel Sci Technol, 19 (1), pp. 393-397; Gallardo, J., Galliano, P., Moreno, R., Durán, A., Bioactive sol-gel coatings for orthopaedic prosthesis (2000) J Sol-Gel Sci Technol, 19 (1-3), pp. 107-111; Gallego, D., Ferrell, N., Sun, Y., Hansford, D., Multilayer micromolding of degradable polymer tissue engineering scaffolds (2008) Mater Sci Eng C, 28 (3), pp. 353-358; Gallego-Perez, D., Higuita-Castro, N., Sharma, S., Reen, R.K., Palmer, A.F., Gooch, K.J., Lee, L.J., Hansford, D.J., High throughput assembly of spatially controlled 3D cell clusters on a micro/nanoplatform (2010) Lab Chip, 10 (6), pp. 775-782; Garcia, C., Ceré, S., Durán, A., Bioactive coatings prepared by sol-gel on stainless steel 316L (2004) J Non-Cryst Solids, 348, pp. 218-224; Healy, K.E., Thomas, C.H., Rezania, A., Kim, J.E., McKeown, P.J., Lom, B., Hockberger, P.E., Kinetics of bone cell organization and mineralization on materials with patterned surface chemistry (1996) Biomaterials, 17 (2), pp. 195-208; Ito, Y., Surface micropatterning to regulate cell functions (1999) Biomaterials, 20 (23-24), pp. 2333-2342; Kim, E.J., Boehm, C.A., Mata, A., Fleischman, A.J., Muschler, G.F., Roy, S., Post microtextures accelerate cell proliferation and osteogenesis (2010) Acta Biomater, 6 (1), pp. 160-169; Lee, E.-J., Lee, S.H., Kim, H.W., Kong, Y.M., Kim, H.-E., Fluoridated apatite coatings on titanium obtained by electronbeam deposition (2005) Biomaterials, 26 (18), pp. 3843-3851; Lim, J.Y., Topographic control of cell response to synthetic materials (2009) Tissue Eng Regen Med, 6 (1), pp. 365-370; Marzolin, C., Smith, S.P., Prentiss, M., Whitesides, G.M., Fabrication of glass microstructures by micro-molding of sol-gel precursors (1998) Adv Mater, 10 (8), pp. 571-574; Mata, A., Boehm, C., Fleischman, A.J., Muschler, G., Roy, S., Growth of connective tissue progenitor cells on microtextured polydimethylsiloxane surfaces (2002) J Biomed Mater Res, 62 (4), pp. 499-506; Mata, A., Kim, E.J., Boehm, C.A., Fleischman, A.J., Muschler, G.F., Roy, S., A three-dimensional scaffold with precise micro-architecture and surface micro-textures (2009) Biomaterials, 30 (27), pp. 4610-4617; Meirelles, L., Currie, F., Jacobsson, M., Albrektsson, T., Wennerberg, A., The effect of chemical and nanotopographical modifications on the early stages of osseointegration (2008) Int J Oral Maxillofac Implants, 23 (4), pp. 641-647; Nayab, S.N., Jones, F.H., Olsen, I., Effects of calcium ion implantation on human bone cell interaction with titanium (2005) Biomaterials, 26 (23), pp. 4717-4727; Pelaez-Vargas, A., Ferrell, N., Fernandes, M.H., Hansford, D., Monteiro, F.J., Cells spreading on micro-fabricated silica thin film coatings (2009) Microsc Microanal, 15 (S3), pp. 77-78; Perrie, W., Rushton, A., Gill, M., Fox, P., O'Neill, W., Femtosecond laser micro-structuring of alumina ceramic (2005) Appl Surf Sci, 248 (1-4), pp. 213-217; Rhee, S.W., Taylor, A.M., Tu, C.H., Cribbs, D.H., Cotman, C.W., Jeon, N.L., Patterned cell culture inside microfluidic devices (2005) Lab Chip, 5 (1), pp. 102-107; Rompen, E., Domken, O., Degidi, M., Pontes, A.E., Piattelli, A., The effect of material characteristics, of surface topography and of implant components and connections on soft tissue integration: A literature review (2006) Clin Oral Implants Res, 17 (S2), pp. 55-67; Sennerby, L., Dental implants: Matters of course and controversies (2000) Periodontol, 47, pp. 9-14; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., Adhesion and microstructural characterization of plasmasprayed hydroxyapatite/glass ceramic coatings onto Ti-6A1-4V substrates (1998) Surf Coat Technol, 102 (3), pp. 191-196; Tan, J., Saltzman, W.M., Biomaterials with hierarchically defined micro- and nanoscale structure (2004) Biomaterials, 25 (17), pp. 3593-3601; Teixeira, S., Monteiro, F.J., Ferraz, M.P., Vilar, R., Eugenio, S., Laser surface treatment of hydroxyapatite for enhanced tissue integration: Surface characterization and osteoblastic interaction studies (2007) J Biomed Mater Res A, 81 (4), pp. 920-929; Vorobyev, A.Y., Guo, C., Femtosecond laser structuring of titanium implants (2007) Appl Surf Sci, 253 (17), pp. 7272-7280; Wang, Y.C., Ho, C.C., Micropatterning of proteins and mammalian cells on biomaterials (2004) Faseb J, 18 (3), pp. 525-527; Wennerberg, A., Albrektsson, T., Andersson, B., Krol, J.J., A histomorphometric study of screw shaped and removal torque titanium implants with three different surface topographies (1995) Clin Oral Impl Res, 6 (1), p. 24; Xia, Y., Whitesides, G.M., Soft lithography (1998) Ann Rev Mater Sci, 28 (1), pp. 153-184; Xia, Y., Whitesides, G.M., Soft lithography (1998) Angew Chem Int Edit, 37 (5), pp. 550-575; Zinger, O., Zhao, G., Schwartz, Z., Simpson, J., Wieland, M., Landolt, D., Boyan, B., Differential regulation of osteoblasts by substrate microstructural features (2005) Biomaterials, 26 (14), pp. 1837-1847
Keywords: AFM; Atomic force microscopy; audiovisual equipment; cell adhesion and proliferation; Cell Culture Techniques; cell proliferation; conference paper; culture technique; cytology; Fluorescence microscopy; Guided tissue regeneration; human; Humans; Microscopy, Atomic Force; Microscopy, Electron, Scanning; Microscopy, Fluorescence; microstamping; Motion Pictures as Topic; myeloid progenitor cell; Myeloid Progenitor Cells; Scanning electron microscopy; SEM; silica sol-gel films; silicon dioxide; Soft lithography; Surface Properties; surface property; Tissue regeneration; tissue scaffold; Tissue Scaffolds

The effect of immobilization of thrombin inhibitors onto self-assembled monolayers on the adsorption and activity of thrombin - Freitas, S.C.; Barbosa, M.A.; Martins, M.C.L. (BiomaterialsBiomaterials, 2010)
Thrombus formation is the major problem associated with biomaterials for blood contact medical devices. The immobilization of inhibitors to thrombin, a serine protease that plays a central role on the coagulation system, on the surface of biomaterials should be a good strategy to avoid blood clotting and increase their hemocompatibility. The aim of this work is the design of a nanostructured surface with capacity to adsorb and inactivate thrombin. The pentapeptide sequence d-Phenylalanine-Proline-Arginine-Proline-Glycine (fPRPG), that was described as a thrombin inhibitor, was immobilized onto tetra(ethylene glycol) terminated self-assembled monolayers (EG4-SAMs). Surface containing different amounts of fPRPG were prepared using different concentrations of N,N′-Carbonyldiimidazole (CDI) during immobilization. The efficiency of fPRPG immobilization was followed using ellipsometry, contact angle measurements, Infrared reflection absorption spectroscopy (IRRAS) and X-ray photoelectron spectroscopy (XPS). Thrombin adsorption was quantified using radiolabelled thrombin and its activity in solution and after adsorption on the developed surfaces was assessed using a chromogenic assay. It was found that, although the immobilization of fPRPG on to EG4-SAMs does not increase its selectivity to thrombin, the activity of the adsorbed thrombin was inhibited in a peptide concentration dependent way. We concluded that SAMs with fPRPG immobilized in high amounts can be used as thrombin-inhibitor surfaces, which is a good step on the development of new surfaces for blood contact devices. © 2010 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2010.01.097PubMed ID: 20153046Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: thrombin, 9002-04-4; Albumins; Gold, 7440-57-5; Immobilized Proteins; Iodine Radioisotopes; Peptides; Solutions; Thrombin, 3.4.21.5References: Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25 (26), pp. 5681-5703;Ratner, B.D., Hoffman, A.F., Schoen, F.J., Lemons, J.L., (2004) Biomaterials science - an introduction to materials in medicine. 2nd ed., , Elsevier Academic Press, San Diego, CA, USA; Bode, W., Structure and interaction modes of thrombin (2006) Blood Cells Mol Dis, 36 (2), pp. 122-130; Huntington, J.A., Molecular recognition mechanisms of thrombin (2005) J Thromb Haemost, 3 (8), pp. 1861-1872; Schwienhorst, A., Direct thrombin inhibitors - a survey of recent developments (2006) Cell Mol Life Sci, 63 (23), pp. 2773-2791; Tseng, P.-Y., Rele, S.S., Sun, X.-L., Chaikof, E.L., Membrane-mimetic films containing thrombomodulin and heparin inhibit tissue factor-induced thrombin generation in a flow model (2006) Biomaterials, 27 (12), pp. 2637-2650; Sperling, C., Salchert, K., Streller, U., Werner, C., Covalently immobilized thrombomodulin inhibits coagulation and complement activation of artificial surfaces in vitro (2004) Biomaterials, 25 (21), pp. 5101-5113; Lin, J.C., Tseng, S.M., Surface characterization and platelet adhesion studies on polyethylene surface with hirudin immobilization (2001) J Mater Sci Mater Med, 12 (9), pp. 827-832; Wendel, H.P., Ziemer, G., Coating-techniques to improve the hemocompatibility of artificial devices used for extracorporeal circulation (1999) Eur J Cardiothorac Surg, 16 (3), pp. 342-350; Werner, C., Maitz, M.F., Sperling, C., Current strategies towards hemocompatible coatings (2007) J Mater Chem, 17 (32), pp. 3376-3384; Weitz, J.I., Crowther, M., Direct thrombin inhibitors (2002) Thromb Res, 106 (3), pp. V275-V284; Di Nisio, M., Middeldorp, S., Büller, H.R., Direct thrombin inhibitors (2005) N Engl J Med, 353 (10), pp. 1028-1040; Stone, S.R., Hofsteenge, J., Kinetics of the inhibition of thrombin by hirudin (1986) Biochemistry, 25 (16), pp. 4622-4628; Grutter, M.G., Priestle, J., Rahuel, J., Grossenbacher, H., Bode, W., Hofsteenge, J., Crystal structure of the thrombin-hirudin complex: a novel mode of serine protease inhibition (1990) EMBO J, 9 (8), pp. 2361-2365; Lahann, J., Plüster, W., Klee, D., Gattner, H.G., Höcker, H., Immobilization of the thrombin inhibitor r-hirudin conserving its biological activity (2001) J Mater Sci Mater Med, 12 (9), pp. 807-810; Phaneuf, M.D., Berceli, S.A., Bide, M.J., Quist, W.C., LoGerfo, F.W., Covalent linkage of recombinant hirudin to poly(ethylene terephthalate) (Dacron): creation of a novel antithrombin surface (1997) Biomaterials, 18 (10), pp. 755-765; Wyers, M.C., Phaneuf, M.D., Rzucidlo, E.M., Contreras, M.A., Logerfo, F.W., Quist, W.C., In vivo assessment of a novel Dacron surface with covalently bound recombinant hirudin (1999) Cardiovasc Pathol, 8 (3), pp. 153-159; Maraganore, J.M., Bourdon, P., Jablonski, J., Ramachandran, K.L., Fenton Ii, J.W., Design and characterization of hirulogs: a novel class of bivalent peptide inhibitors of thrombin (1990) Biochemistry, 29 (30), pp. 7095-7101; Maraganore, J.M., Chao, B., Joseph, M.L., Jablonski, J., Ramachandran, K.L., Anticoagulant activity of synthetic hirudin peptides (1989) J Biol Chem, 264 (15), pp. 8692-8698; Sun, X., Sheardown, H., Tengvall, P., Brash, J.L., Peptide modified gold-coated polyurethanes as thrombin scavenging surfaces (2000) J Biomed Mater Res, 49 (1), pp. 66-78; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111 (1), pp. 321-335; Herrwerth, S., Eck, W., Reinhardt, S., Grunze, M., Factors that determine the protein resistance of oligoether self-assembled monolayers - internal hydrophilicity, terminal hydrophilicity, and lateral packing density (2003) J Am Chem Soc, 125 (31), pp. 9359-9366; Lottenberg, R., Christensen, U., Jackson, C.M., Coleman, P.L., Assay of coagulation proteases using peptide chromogenic and fluorogenic substrates (1981) Meth Enzymol, 80 (PART C), pp. 341-361; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67 A (1), pp. 158-171; Martins, M.C.L., Curtin, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88 (1), pp. 162-173; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Rahmelow, K., Hubner, W., Ackermann, T., Infrared absorbances of protein side chains (1998) Anal Biochem, 257 (1), pp. 1-11; Barth, A., The infrared absorption of amino acid side chains (2000) Prog Biophys Mol Biol, 74 (3-5), pp. 141-173; Li, L., Chen, S., Zheng, J., Ratner, B.D., Jiang, S., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: the molecular basis for nonfouling behavior (2005) J Phys Chem B, 109 (7), pp. 2934-2941; Beamson, G., Briggs, D., (1992) High resolution XPS of organic polymers, , John Wiley and Sons, Ltd;, New York; Adden, N., Gamble, L.J., Castner, D.G., Hoffmann, A., Gross, G., Menzel, H., Phosphonic acid monolayers for binding of bioactive molecules to titanium surfaces (2006) Langmuir, 22 (19), pp. 8197-8204; Sousa, S.R., Moradas-Ferreira, P., Saramago, B., Viseu Melo, L., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20 (22), pp. 9745-9754; Di Cera, E., Thrombin interactions (2003) Chest, 124 (SUPPL. 3), pp. 11S-17S; Markwardt, F., Historical perspective of the development of thrombin inhibitors (2002) Pathophysiol Haemost Thromb, 32 (SUPPL. 3), pp. 15-22; Hearn, M.T., 1,1′-Carbonyldiimidazole-mediated immobilization of enzymes and affinity ligands (1987) Methods Enzymol, 135, pp. 102-117; Stöllner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1′-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304 (2), pp. 157-165; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on Cibacron Blue F3G-A immobilized onto oligo(ethylene glycol)- terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14 (11), pp. 945-954; Dee, K.C., Puleo, D.A., Bizios, R., (2002) An introduction to tissue-biomaterial interactions, , Wiley-Liss, Inc; Malmsten, M., Lassen, B., Competitive adsorption at hydrophobic surfaces from binary protein systems (1994) J Colloid Interface Sci, 166 (2), pp. 490-498
Keywords: Absorption spectroscopy; Adsorption; adsorption kinetics; Albumins; Amino Acid Sequence; Amino acids; Angle measurement; article; Biomaterials; Blood; Blood clotting; Blood contact; Carbonyldiimidazole; Coagulation; Coagulation system; concentration (parameters); Concentration-dependent; Contact angle; D-phenylalanine; ellipsometry; Ethylene; Ethylene Glycol; ethylene glycol derivative; gold; Hemocompatibility; Humans; imidazole derivative; Immobilized Proteins; Infrared reflection absorption spectroscopy; infrared spectroscopy; Iodine Radioisotopes; isotope labeling; Medical Devices; monolayer culture; nanoanalysis; Nanostructured surface; peptide; Peptide immobilization; Peptides; phenylalanylprolylarginylprolylglycine; Phosphatases; priority journal; Protein adsorption; protein assembly; protein function; protein immobilization; quantitative study; Sams; Self assembled monolayers; Self-assembled monolayers; Serine protease; Solubility; Solutions; Spectroscopy, Fourier Transform Infrared; Surface functionalization; Surface Properties; Tetra; tetra(ethylene glycol); Thrombin; thrombin inhibitor; Thrombin inhibitors; Thrombus formation; unclassified drug; X ray photoelectron spectroscopy

Effect of nanoscale topography on fibronectin adsorption, focal adhesion size and matrix organisation - González-García, C.; Sousa, S.R.; Moratal, D.; Rico, P.; Salmerón-Sánchez, M. (Colloids and Surfaces B: BiointerfacesColloids Surf. B Biointerfaces, 2010)
Phase separation of PLLA/PS (50/50, w/w) solutions during a spin-casting process gives rise to well-defined nanotopographies of 14, 29 and 45. nm deep pits depending on the concentration of the solution. Their influence on the biological activity of fibronectin (FN) was investigated. FN adsorption was quantified by radiolabelling the protein. The amount of adsorbed FN was higher on the 14. nm deep pit nanotopography than on the other two surfaces. FN distribution between valleys and peaks was investigated by AFM combined with image analysis. FN tends to adsorb preferentially on the valleys of the nanotopography only for the 14. nm system and when adsorbed from solutions of concentration lower than 10μg/ml. Higher concentration of the FN solution leads to evenly distribution of the protein throughout the surface; moreover, there is no difference in the distribution of the protein between valleys and peaks for the other two systems (29 and 45. nm) irrespective of the concentration of the FN solution. The biological activity of the adsorbed protein layer was assessed by investigating MC3T3 osteoblast-like cells adhesion, FN reorganisation and late matrix formation on the different substrates. Even if initial cell adhesion is excellent for every substrate, the size of the focal adhesion plaques increases as the size of the pits in the nanotopography does. This is correlated to FN reorganisation, which only takes places on the 29 and 45. nm deep pits surfaces, where enhanced late matrix production was also found. © 2010 Elsevier B.V.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: CSBBEdoi: 10.1016/j.colsurfb.2010.01.021PubMed ID: 20185279Language of Original Document: EnglishCorrespondence Address: Rico, P.; Center for Biomaterials and Tissue Engineering, Universidad Politécnica de Valencia, 46022 Valencia, Spain; email: parico@upvnet.upv.esChemicals/CAS: fibronectin, 86088-83-7; polylactic acid, 26100-51-6; polystyrene, 9003-53-6; Fibronectins; ProteinsReferences: Spie, J., (2002) Ann. N. Y. Acad. Sci., 961, p. 1;Griffin, L., Naughton, G., (2002) Science, 259, p. 1009; Grinnell, F., (1986) J. Cell Biol., 103, p. 2697; Hynes, R.O., (2002) Cell, 110, p. 673; Wong, J.Y., Leach, J.B., Brown, X.Q., (2004) Surf. Sci., 570, p. 119; Schwarz, U.S., Bischofs, I.B., (2005) Med. Eng. Phys., 27, p. 763; Ohara, P.T., Buck, R.C., (1979) Exp. Cell Res., 121, p. 235; Lim, J.Y., Donahue, H.J., (2007) Tissue Eng., 13, p. 1879; Affrossman, S., Jerome, R., O'Neill, S.A., Schmitt, T., Stamm, M., (2000) Colloid Polym. Sci., 278, p. 888; Denis, F.A., Hanarp, P., Sutherland, D.S., Dufrene, Y.F., (2002) Nanoletters, 2, p. 1419; Vieu, C., Carcenac, F., Pepin, A., Chen, Y., Mejias, M., Lebib, A., Manin-Ferlazzo, L., Launois, H., (2000) Appl. Surf. Sci., 164, p. 111; Kriparamanan, R., Aswath, P., Zhou, A., Tang, L., Nguyen, K.T., (2006) J. Nanosci. Nanotechnol., 6, p. 1905; Dalby, M.J., Giannaras, D., Riehle, M.O., Gadegaard, N., Affrossman, S., Curtis, A.S.G., (2004) Biomaterials, 25, p. 77; Lim, J.Y., Dreiss, D., Zhou, Z., Hansen, J.C., Siedlecki, C.A., Hengstebeck, R.W., Cheng, J., Donahue, H.J., (2007) Biomaterials, 28, p. 1787; Dalby, M.J., Hart, A., Yarwood, S.J., (2008) Biomaterials, 29, p. 282; Zinger, O., Zhao, G., Schwartz, Z., Simpson, J., Wieland, M., Landlolt, D., Boyan, B., (2005) Biomaterials, 26, p. 1837; Dalby, M.J., Gadegaard, N., Tare, R., Andar, A., Riehle, M.O., Herzyk, P., Wilkinson, C.D.W., Oreffo, R.O.C., (2007) Nat. Mater., 9, p. 997; Dalby, M.J., McCloy, D., Robertson, M., Wilkinson, C.D.W., Oreffo, R.O.C., (2006) Biomaterials, 27, p. 1306; Pirouz-Dolatshahi, A., Rechendorff, K., Hovgaard, M.B., Foss, M., Chevallier, J., Besenbacher, F., (2008) Colloid Surf. B, 66, p. 53; Khor, H.L., Kukula, H., Tamada, K., Knoll, W., Moeller, M., Hutmacher, D.W., (2007) Biomacromolecules, 8, p. 1530; Cai, K., Bossert, J., Jandt, K., (2006) Colloid Surf. B, 49, p. 136; (1993), p. 64. , Iodine-125, Amersham International, Little Chalfont, Buckinghamshire, U.K.Sousa, S.R., Brás, M., Moradas-Ferreira, P., Barbosa, M.A., (2007) Langmuir, 23, p. 7046; Otsu, N.A., (1979) IEEE Trans. Syst. Man Cybern., 9, p. 62; Gonzalez, R.C., Woods, R.E., Eddins, S.L., (2003) Digital Image Processing Using MATLAB, , Prentice-Hall, Upper Saddle River, NJ; Gonzalez, R.C., Woods, R.E., (2007) Digital Image Processing, , Prentice-Hall, Upper Saddle River, NJ; (2006), MATLAB Image Processing Toolbox User's Guide, The MathWorks, Inc., Natick, MAAllen, L.T., Tosetto, M., Miller, I.S., O'Connor, D.P., Penney, S.C., Lynch, I., Keenan, A.K., Gallagher, W.M., (2006) Biomaterials, 27, p. 3096; Gugutkov, D., Altankov, G., Rodríguez Hernández, J.C., Monleón Pradas, M., Salmerón Sánchez, M., (2010) J. Biomed. Mater. Res. A, 92, p. 322; Rico, P., Rodríguez Hernández, J.C., Moratal, D., Monleón Pradas, M., Salmerón Sánchez, M., (2009) Macromol. Biosci., 9, p. 766; Keselowsky, B.G., Collard, D.M., García, A.J., (2003) J. Biomed. Mater. Res. A, 66, p. 247; Lee, M.H., Ducheyne, P., Lynch, L., Boettiger, D., Composto, R.J., (2006) Biomaterials, 27, p. 1907; Costa Martínez, E., Rodríguez Hernández, J.C., Machado, M., Mano, J., Gómez Ribelles, J.L., Monleón Pradas, M., Salmerón Sánchez, M., (2008) Tissue Eng., 14, p. 1751; Lim, J.Y., Hansen, J.C., Siedlecki, C.A., Hengstebeck, R.A., Cheng, J., Winograd, N., (2005) Biomacromolecules, 6, p. 3319; Liu, X., Lim, J.Y., Donahue, H.J., Dhurjati, R., Maestro, A.M., Vogler, E.A., (2007) Biomaterials, 28, p. 4535; Dalby, M.J., Yarwood, S.J., Riehle, M.O., Johnstone, H.J., Affressman, S., Curtis, A.S., (2002) Exp. Cell Res., 276, p. 1; Dalby, M.J., Childs, S., Riehle, M.O., Johnston, H.J.H., Affrossman, S., (2003) Biomaterials, 24, p. 927; Dalby, M.J., McCloy, D., Robertson, M., Agheli, H., Sutherland, D., Affrossman, S., Oreffo, R.O.C., (2006) Biomaterials, 27, p. 2980; Dalby, M.J., (2005) Med. Eng. Phys., 27, p. 730; Galbraith, C.G., Yamada, K.M., Sheetz, M.P., (2002) J. Cell Biol., 159, p. 695; Balaban, N.Q., Schwarz, U.S., Riveline, D., Goichberg, P., Tzur, G., Sabanay, I., (2001) Nat. Cell Biol., 3, p. 466; Pegueroles, M., Aparicio, C., Bosio, M., Engel, E., Gil, F.J., Planell, J.A., Altankov, G., Acta Biomater. (). doi:10.1016/j.actbio.2009.07.030Altankov, G., Groth, T., (1994) J. Mater. Sci. Mater. Med., 5, p. 732; Altankov, G., Groth, T., (1996) J. Mater. Sci. Mater. Med., 7, p. 425; Altankov, G., Grinnell, F., Groth, T., (1996) J. Biomed. Mater. Res., 30, p. 385; Tzoneva, R., Groth, T., Altankov, G., Paul, D., (2002) J. Mater. Sci. Mater. Med., 13, p. 1235; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., (2005) Biomaterials, 26, p. 3891; Luthen, F., Lange, R., Becker, P., Rychly, J., Beck, U., Nebe, J.G.B., (2005) Biomaterials, 26, p. 2423; Geiger, B., Bershadsky, A., Pankov, R., Yamada, K.M., (2001) Nat. Rev. Mol. Cell Biol., 2, p. 793; Altankov, G., Groth, T., (1996) J. Biomater. Sci. Polym. Ed., 8, p. 299
Keywords: 3T3 Cells; Adhesion; Adsorption; AFM; animal cell; Animals; article; Atomic force microscopy; Bioactivity; Biological activities; biological activity; Casting process; cell adhesion; Cell Line; concentration (parameters); Concentration (process); Concentration of; Deep pit; Different substrates; Electric currents; extracellular matrix; Fibronectin; Fibronectin adsorption; Fibronectins; focal adhesion; Focal adhesion plaques; Focal adhesions; Humans; Image analysis; Image Processing, Computer-Assisted; isotope labeling; Landforms; matrix; Matrix formation; Mice; Microscopy, Atomic Force; nanomaterial; Nanoscale topography; Nanotechnology; Nanotopographies; Nanotopography; nonhuman; osteoblast; Osteoblast-like cells; Osteoblasts; Phase separation; polylactic acid; polystyrene; priority journal; Protein adsorption; Protein layers; protein localization; Proteins; Radiolabelling; Reorganisation; Substrates; Surface Properties

Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds - Barbosa, J.N.; Amaral, I.F.; Águas, A.P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
The effect of the degree of acetylation (DA) of 3D chitosan (Ch) scaffolds on the inflammatory reaction was investigated. Chitosan porous scaffolds with DAs of 4 and 15% were implanted using a subcutaneous air-pouch model of inflammation. The initial acute inflammatory response was evaluated 24 and 48 h after implantation. To characterize the initial response, the recruitment and adhesion of inflammatory cells to the implant site was studied. The fibrous capsule formation and the infiltration of inflammatory cells within the scaffolds were evaluated for longer implantation times (2 and 4 weeks). Chitosan with DA 15% attracted the highest number of leukocytes to the implant site. High numbers of adherent inflammatory cells were also observed in this material. For longer implantation periods Ch scaffolds with a DA of 15% induced the formation of a thick fibrous capsule and a high infiltration of inflammatory cells within the scaffold. Our results indicate that the biological response to implanted Ch scaffolds was influenced by the DA. Chitosan with a DA of 15% induce a more intense inflammatory response when compared with DA 4% Ch. Because inflammation and healing are interrelated, this result may provide clues for the relative importance of acetyl and amine functional groups in tissue repair and regeneration. © 2009 Wiley Periodicals, Inc.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32499PubMed ID: 19484769Language of Original Document: EnglishCorrespondence Address: Barbosa, J. N.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; Chitosan, 9012-76-4References: Sefton, M.V., Babensee, J.E., Woodhouse, K.A., Innate and adaptative immune responses in tissue engineering (2008) Semin Immunol, 20, pp. 83-85;VandeVord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59, pp. 585-590; Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110; Babensee, J.E., Anderson, J.M., McIntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliv Rev, 33, pp. 111-139; Ueno, H., Mori, T., Fujinaga, T., Topical formulations and wound healing applications of chitosan (2001) Adv Drug Deliv Rev, 52, pp. 105-115; Kim, I.Y., Seo, S.J., Moon, H.S., Yoo, M.K., Park, I.Y., Kim, B.C., Cho, C.S., Chitosan and its derivatives for tissue engineering applications (2008) Biotechnol Adv, 26, pp. 1-21; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18, pp. 567-575; Peluso, G., Petillo, O., Ranieri, M., Santin, M., Ambrosio, L., Calabro, D., Avallone, B., Balsamo, G., Chitosan-mediated stimulation of macrophage function (1994) Biomaterials, 15, pp. 1215-1220; Porporatto, C., Bianco, I.D., Riera, C.M., Correa, S.G., Chitosan induces different L-arginine metabolic pathways in resting and in.ammatory macrophages (2003) Biochem Biophys Res Commun, 304, pp. 266-272; Mori, T., Okumura, M., Matsuura, M., Ueno, K., Tokura, S., Okamoto, Y., Minami, S., Fujinaga, T., Effects of chitin and its derivatives on the proliferation and cytokine production of fibroblasts in vitro (1997) Biomaterials, 18, pp. 947-951; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Vachoud, L., Zydowicz, N., Domard, A., Formation and characterisation of a physical chitin gel (1997) Carbohydr Res, 302, pp. 169-177; Suh, J.K.F., Matthew, H.W.T., Application of chitosan-based polysaccharide biomaterials in cartilage tissue engineering: A review (2000) Biomaterials, 21, pp. 2589-2598; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Haishima, Y., Endotoxin contamination in wound dressings made of natural biomaterials (2003) J Biomed Mater Res Part B: Appl Biomater, 66 B, pp. 347-355; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Castro, A.G., Esaguy, N., Macedo, P.M., Aguas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Tang, L.P., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Tang, L.P., Jennings, T.A., Eaton, J.W., Mast cells mediate acute inflammatory responses to implanted biomaterials (1998) Proc Natl Acad Sci USA, 95, pp. 8841-8846; Food and Drug Administration (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test as an End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services PHS, Washington, DC: US Department of Health and Human Services;; Hooper, K.A., Nickolas, T.L., Yurkow, E.J., Kohn, J., Laskin, D.L., Characterization of the inflammatory response to biomaterials using a rodent air pouch model (2000) J Biomed Mater Res, 50, pp. 365-374; Wooley, P.H., Morren, R., Andary, J., Sud, S.A., Yang, S.Y., Mayton, L., Markel, D., Nasser, S., Inflammatory responses to orthopaedic biomaterials in the murine air pouch (2002) Biomaterials, 23, pp. 517-526; Amaral, I.F., Sampaio, P., Barbosa, M.A., Three-dimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2006) J Biomed Mater Res, 76 A, pp. 335-346. , Part A; Thomsen, P., Gretzer, C., Macrophage interactions with modified material surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Hu, W.J., Eaton, J.W., Tang, L.P., Molecular basis of biomaterial - mediated foreign body reactions (2001) Blood, 98, pp. 1231-1238; Benesch, J., Tengvall, P., Blood protein adsorption onto chitosan (2002) Biomaterials, 23, pp. 2561-2568; Hidaka, Y., Ito, M., Mori, K., Yagasaki, H., Kafrawy, A.H., Histopathological and immunohistochemical studies of membranes of deacetylated chitin derivatives implanted over rat calvaria (1999) J Biomed Mater Res, 46, pp. 418-423; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cell osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation (2005) J Biomed Mater Res, 75 A, pp. 387-397. , Part A; Ueno, H., Murakami, M., Okumura, M., Kadosawa, T., Uede, T., Fujinaga, T., Chitosan accelerates the production of osteopontin from polymorphonuclear leukocytes (2001) Biomaterials, 22, pp. 1667-1673
Keywords: acetic acid derivative; Acetylation; Acute inflammatory response; amine; Amine functional groups; animal cell; animal experiment; animal tissue; Animals; article; Biological materials; Biological response; Biomaterials; cell adhesion; cell infiltration; Chitin; chitosan; Chitosan scaffold; Degree of acetylation; Fibrous capsule; Fibrous capsule formation; freeze drying; Functional groups; Hydrogels; implant; implantation; Implantation periods; Implants, Experimental; Inflammation; Inflammatory cells; Inflammatory reaction; Inflammatory response; leukocyte count; Leukocytes; male; Mice; Mice, Inbred BALB C; Microscopy, Electron, Scanning; mouse; nonhuman; Pathology; porosity; Porous scaffold; Prosthesis Implantation; Relative importance; Scaffolds; Subcutaneous Tissue; Surface Properties; Three dimensional; Tissue regeneration; tissue repair; Tissue response; Tissue responses; Tissue Scaffolds

Functionalization of poly(amidoamine) dendrimers with hydrophobic chains for improved gene delivery in mesenchymal stem cells - Santos, J.L.; Oliveira, H.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2010)
A new family of gene delivery vectors is synthesized consisting of a medium-size generation PAMAM dendrimer (generation 5, with amine termini) core randomly linked at the periphery to hydrophobic chains that vary in length (12 to 16 carbon alkyl chains) and number (from 4.2 to 9.7 in average). The idea subjacent to the present work is to join the advantages of the cationic nature of the dendrimer with the capacity of lipids to interact with biological membranes. Unlike other amphiphilic systems designed for the same purpose, where the hydrophobic and hydrophilic moieties coexist in opposite sides, the present vectors have a hydrophilic interior and a hydrophobic corona. The vectors are characterized in respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA are analyzed concerning their size, ζ-potential, resistance to serum nucleases, capacity of being internalized by cells and transfection efficiency. These new vectors show a remarkable capacity for mediating the internalization of pDNA with minimum cytotoxicity, being this effect positively correlated with the -CH 2- content present in the hydrophobic corona. Gene expression in MSCs, a cell type with relevancy in the regenerative medicine clinical context, is also enhanced using the new vectors but, in this case, the higher efficiency is shown by the vectors containing the smallest hydrophobic chains. © 2010 Elsevier B.V.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2010.01.034PubMed ID: 20138937Language of Original Document: EnglishCorrespondence Address: Tomás, H.; CQM - Centro de Química da Madeira, MMRG, Departamento de Química, Universidade da Madeira, Campus Universitário da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: lipid, 66455-18-3; nuclease, 9026-81-7; Cations; DNA, 9007-49-2; Dendrimers; Lipids; PAMAM StarburstReferences: Segura, T., Shea, L.D., Materials for non-viral gene delivery (2001) Annu. Rev. Mat. Res., 31, pp. 25-46;Mastrobattista, E., Bravo, S.A., van der Aa, M., Crommelin, D.J.A., Nonviral gene delivery systems: from simple transfection agents to artificial viruses (2005) Drug Discov. Today Technol., 2, pp. 103-109; Colella, P., Cotugno, G., Auricchio, A., Ocular gene therapy: current progress and future prospects (2009) Trends Mol. Med., 15, pp. 23-31; Scanlon, K.J., Cancer gene therapy: challenges and opportunities (2004) Anticancer Res., 24, pp. 501-504; Gersbach, C.A., Phillips, J.E., Garcia, A.J., Genetic engineering for skeletal regenerative medicine (2007) Annu. Rev. Biomed. Eng., 9, pp. 87-119; Heyde, M., Partridge, K.A., Oreffo, R.O., Howdle, S.M., Shakesheff, K.M., Garnett, M.C., Gene therapy used for tissue engineering applications (2007) J. Pharm. Pharmacol., 59, pp. 329-350; Gafni, Y., Turgeman, G., Liebergal, M., Pelled, G., Gazit, Z., Gazit, D., Stem cells as vehicles for orthopedic gene therapy (2004) Gene Ther., 11, pp. 417-426; Vaananen, H.K., Mesenchymal stem cells (2005) Ann. Med., 37, pp. 469-479; Phillips, J.E., Gersbach, C.A., Garcia, A.J., Virus-based gene therapy strategies for bone regeneration (2007) Biomaterials, 28, pp. 211-229; Lundstrom, K., Latest development in viral vectors for gene therapy (2003) Trends Biotechnol., 21, pp. 117-122; Noel, D., Gazit, D., Bouquet, C., Apparailly, F., Bony, C., Plence, P., Millet, V., Jorgensen, C., Short-term BMP-2 expression is sufficient for in vivo osteochondral differentiation of mesenchymal stem cells (2004) Stem Cells, 22, pp. 74-85; Mintzer, M.A., Simanek, E.E., Nonviral vectors for gene delivery (2009) Chem. Rev., 109, pp. 259-302; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8, pp. 235-245; McMahon, J.M., Conroy, S., Lyons, M., Greiser, U., O'Shea, C., Strappe, P., Howard, L., O'Brien, T., Gene transfer into rat mesenchymal stem cells: a comparative study of viral and nonviral vectors (2006) Stem Cells Dev., 15, pp. 87-96; Jang, W.-D., Selim, K.M.K., Lee, C.-H., Kang, I.-K., Bioinspired application of dendrimers: from bio-mimicry to biomedical applications (2009) Prog. Polym. Sci., 34, pp. 1-23; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Deliv. Rev., 57, pp. 2106-2129; Caminade, A.M., Turrin, C.O., Majoral, J.P., Dendrimers and DNA: combinations of two special topologies for nanomaterials and biology (2008) Chemistry, 14, pp. 7422-7432; Dufes, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Deliv. Rev., 57, pp. 2177-2202; Guillot, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31, pp. 1111-1127; Lechardeur, D., Verkman, A.S., Lukacs, G.L., Intracellular routing of plasmid DNA during non-viral gene transfer (2005) Adv. Drug Deliv. Rev., 57, pp. 755-767; Smith, D.K., Dendrimers and the double helix - from DNA binding towards gene therapy (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Dobrovolskaia, M.A., McNeil, S.E., Immunological properties of engineered nanomaterials (2007) Nat. Nanotechnol., 2, pp. 469-478; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker, J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pego, A.P., Granja, P.L., Tomas, H., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors (2009) J. Control. Release, 134, pp. 141-148; Dennig, J., Duncan, E., Gene transfer into eukaryotic cells using activated polyamidoamine dendrimers (2002) J. Biotechnol., 90, pp. 339-347; Kono, K., Akiyama, H., Takahashi, T., Takagishi, T., Harada, A., Transfection activity of polyamidoamine dendrimers having hydrophobic amino acid residues in the periphery (2005) Bioconjug. Chem., 16, pp. 208-214; Takahashi, T., Harada, A., Emi, N., Kono, K., Preparation of efficient gene carriers using a polyamidoamine dendron-bearing lipid: improvement of serum resistance (2005) Bioconjug. Chem., 16, pp. 1160-1165; Takahashi, T., Kojima, C., Harada, A., Kono, K., Alkyl chain moieties of polyamidoamine dendron-bearing lipids influence their function as a nonviral gene vector (2007) Bioconjug. Chem., 18, pp. 1349-1354; Takahashi, T., Kono, K., Itoh, T., Emi, N., Takagishi, T., Synthesis of novel cationic lipids having polyamidoamine dendrons and their transfection activity (2003) Bioconjug. Chem., 14, pp. 764-773; Jones, S.P., Gabrielson, N.P., Pack, D.W., Smith, D.K., Synergistic effects in gene delivery - a structure-activity approach to the optimisation of hybrid dendritic-lipidic transfection agents (2008) Chem. Commun., 39, pp. 4700-4702; Shah, D.S., Sakthivel, T., Toth, I., Florence, A.T., Wilderspin, A.F., DNA transfection and transfected cell viability using amphipathic asymmetric dendrimers (2000) Int. J. Pharm., 208, pp. 41-48; Ahmad, A., Evans, H.M., Ewert, K., George, C.X., Samuel, C.E., Safinya, C.R., New multivalent cationic lipids reveal bell curve for transfection efficiency versus membrane charge density: lipid-DNA complexes for gene delivery (2005) J. Gene Med., 7, pp. 739-748; Ewert, K.K., Evans, H.M., Zidovska, A., Bouxsein, N.F., Ahmad, A., Safinya, C.R., A columnar phase of dendritic lipid-based cationic liposome-DNA complexes for gene delivery: hexagonally ordered cylindrical micelles embedded in a DNA honeycomb lattice (2006) J. Am. Chem. Soc., 128, pp. 3998-4006; Guillot, M., Eisler, S., Weller, K., Merkle, H.P., Gallani, J.L., Diederich, F., Effects of structural modification on gene transfection and self-assembling properties of amphiphilic dendrimers (2006) Org. Biomol. Chem., 4, pp. 766-769; Joester, D., Losson, M., Pugin, R., Heinzelmann, H., Walter, E., Merkle, H.P., Diederich, F., Amphiphilic dendrimers: novel self-assembling vectors for efficient gene delivery (2003) Angew. Chem. Int. Ed., 42, pp. 1486-1490; Alvarez, E., Girones, N., Davis, R.J., Inhibition of the receptor-mediated endocytosis of diferric transferrin is associated with the covalent modification of the transferrin receptor with palmitic acid (1990) J. Biol. Chem., 265, pp. 16644-16655; Jevprasesphant, R., Penny, J., Attwood, D., McKeown, N.B., D'Emanuele, A., Engineering of dendrimer surfaces to enhance transepithelial transport and reduce cytotoxicity (2003) Pharm. Res., 20, pp. 1543-1550; Snyder, S.L., Sobocinski, P.Z., An improved 2,4,6-trinitrobenzenesulfonic acid method for the determination of amines (1975) Anal. Biochem., 64, pp. 284-288; Lapidot, Y., Rappoport, S., Wolman, Y., Use of esters of N-hydroxysuccinimide in the synthesis of N-acylamino acids (1967) J. Lipid. Res., 8, pp. 142-145; Gao, X., Huang, L., Potentiation of cationic liposome-mediated gene delivery by polycations (1996) Biochemistry, 35, pp. 1027-1036; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J. Cell Biochem., 72, pp. 396-410; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., Resazurin metabolism assay is a new sensitive alternative test in isolated pig cornea (2003) Toxicol. Sci., 72, pp. 122-129; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., Enhanced ectopic bone formation using a combination of plasmid DNA impregnation into 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Wong, S.Y., Pelet, J.M., Putnam, D., Polymer systems for gene delivery - past, present, and future (2007) Prog. Polym. Sci., 32, pp. 799-837; Abbasi, M., Uludag, H., Incani, V., Hsu, C.Y., Jeffery, A., Further investigation of lipid-substituted poly(L-lysine) polymers for transfection of human skin fibroblasts (2008) Biomacromolecules, 9, pp. 1618-1630; Sorgi, F.L., Bhattacharya, S., Huang, L., Protamine sulfate enhances lipid-mediated gene transfer (1997) Gene Ther., 4, pp. 961-968; Lampela, P., Soininen, P., Urtti, A., Männistö, P.T., Raasmaja, A., Synergism in gene delivery by small PEIs and three different nonviral vectors (2004) Int. J. Pharm., 270, pp. 175-184; Brito, L., Little, S., Langer, R., Amiji, M., Poly(β-amino ester) and cationic phospholipid-based lipopolyplexes for gene delivery and transfection in human aortic endothelial and smooth muscle cells (2008) Biomacromolecules, 9, pp. 1179-1187; Hardy, J.G., Love, C.S., Gabrielson, N.P., Pack, D.W., Smith, D.K., Synergistic effects on gene delivery - co-formulation of small disulfide-linked dendritic polycations with Lipofectamine 2000TM (2009) Org. Biomol. Chem., 7, pp. 789-793; Callow, P., Fragneto, G., Cubitt, R., Barlow, D.J., Lawrence, M.J., Timmins, P., Interaction of cationic lipid vesicles with model cell membranes - as determined by neutron reflectivity (2005) Langmuir, 21, pp. 7912-7920; Malik, N., Wiwattanapatapee, R., Klopsch, R., Lorenz, K., Frey, H., Weener, J.W., Meijer, E.W., Duncan, R., Dendrimers: relationship between structure and biocompatibility in vitro, and preliminary studies on the biodistribution of 125I-labelled polyamidoamine dendrimers in vivo (2000) J. Control. Release, 65, pp. 133-148
Keywords: amphophile; animal cell; animal experiment; article; Biological membranes; Biomedical applications; cation; Cations; Cell culture; cell membrane transport; cell type; Cellular uptake; controlled study; Cytotoxicity; dendrimer; Dendrimers; DNA; DNA binding; Dyes; Functional polymers; Gene delivery; gene delivery system; gene expression; Gene therapy; Gene transfer; Gene Transfer Techniques; gene vector; Genes; genetic transfection; Genetic Vectors; Humans; Hydrocarbons; hydrophilicity; hydrophobicity; internalization; lipid; Lipids; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; nuclease; Nucleic acids; plasmid DNA; Plasmids; Poly(amidoamine) dendrimers; polyamidoamine; Polyamidoamine dendrimers; priority journal; rat; Regenerative Medicine; Stem cells; Transfection; Vectors; Zeta potential

Heparinized hydroxyapatite/collagen three-dimensional scaffolds for tissue engineering - Teixeira, S.; Yang, L.; Dijkstra, P.J.; Ferraz, M.P.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2010)
Currently, in bone tissue engineering research, the development of appropriate biomaterials for the regeneration of bony tissues is a major concern. Bone tissue is composed of a structural protein, collagen type I, on which calcium phosphate crystals are enclosed. For tissue engineering, one of the most applied strategies consists on the development and application of three dimensional porous scaffolds with similar composition to the bone. In this way, they can provide a physical support for cell attachment, proliferation, nutrient transport and new bone tissue infiltration. Hydroxyapatite is a calcium phosphate with a similar composition of bone and widely applied in several medical/dentistry fields. Therefore, in this study, hydroxyapatite three dimensional porous scaffolds were produced using the polymer replication method. Next, the porous scaffolds were homogeneously coated with a film of collagen type I by applying vacuum force. Yet, due to collagen degradability properties, it was necessary to perform an adequate crosslinking method. As a result, N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) was employed as an efficient and non-toxic crosslinking method in this research. The composites were characterized by means of SEM, DSC and TNBS. Furthermore, heparin was incorporated in order to accomplish sustained delivery of a growth factor of interest namely, bone morphogenetic proteins (BMP-2). BMP-2 binding and release of non-heparinized and heparinized scaffolds was evaluated at specific time points. The incorporation of heparin leads to a reduced initial burst phase when compared to the non heparinized materials. The results show a beneficial effect with the incorporation of heparin and its potential as a localized drug delivery system for the sustained release of growth factors. © 2010 Springer Science+Business Media, LLC.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-010-4097-2PubMed ID: 20596760Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; Divisão de Biomateriais, INEB-Instituto de Engenharia Biomédica, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: sandra_teixeira3@yahoo.comChemicals/CAS: collagen, 9007-34-5; cyanamide, 151-51-9, 420-04-2; heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; hydroxyapatite, 1306-06-5, 51198-94-8; n hydroxysuccinimide, 6066-82-6; trinitrobenzenesulfonic acid, 16655-63-3, 2508-19-2; Biocompatible Materials; Bone Substitutes; Collagen, 9007-34-5; Cross-Linking Reagents; Durapatite, 1306-06-5; Heparin, 9005-49-6; PolymersReferences: Rose, F.R., Cyster, L.A., Grant, D.M., Scotchford, C.A., Howdle, S.M., Shakesheff, K.M., In vitro assessment of cell penetration into porous hydroxyapatite scaffolds with a central aligned channel (2004) Biomaterials, 25 (24), pp. 5507-5514. , DOI 10.1016/j.biomaterials.2004.01.012, PII S0142961204000134;Hong, Z., Zhang, P., He, C., Qiu, X., Liu, A., Chen, L., Chen, X., Jing, X., Nano-composite of poly(L-lactide) and surface grafted hydroxyapatite: Mechanical properties and biocompatibility (2005) Biomaterials, 26 (32), pp. 6296-6304. , DOI 10.1016/j.biomaterials.2005.04.018, PII S0142961205003297; Ignjatovic, N., Tomic, S., Dakic, M., Miljkovic, M., Plavsic, M., Uskokovic, D., Synthesis and properties of hydroxyapatite/poly-L-lactide composite biomaterials (1999) Biomaterials, 20 (9), pp. 809-816. , DOI 10.1016/S0142-9612(98)00234-8, PII S0142961298002348; Kothapalli, C.R., Shaw, M.T., Wei, M., Biodegradable HA-PLA 3-D porous scaffolds: Effect of nano-sized filler content on scaffold properties (2005) Acta Biomaterialia, 1 (6), pp. 653-662. , DOI 10.1016/j.actbio.2005.06.005, PII S1742706105000978; Liao, S., Wang, W., Uo, M., Ohkawa, S., Akasaka, T., Tamura, K., Cui, F., Watari, F., A three-layered nano-carbonated hydroxyapatite/collagen/PLGA composite membrane for guided tissue regeneration (2005) Biomaterials, 26 (36), pp. 7564-7571. , DOI 10.1016/j.biomaterials.2005.05.050, PII S0142961205004199; Maeda, H., Kasuga, T., Hench, L.L., Preparation of poly(L-lactic acid)-polysiloxane-calcium carbonate hybrid membranes for guided bone regeneration (2006) Biomaterials, 27 (8), pp. 1216-1222. , DOI 10.1016/j.biomaterials.2005.08.010, PII S0142961205007829; Kong, L., Gao, Y., Cao, W., Gong, Y., Zhao, N., Zhang, X., Preparation and characterization of nano-hydroxyapatite/chitosan composite scaffolds (2005) Journal of Biomedical Materials Research - Part A, 75 (2), pp. 275-282. , DOI 10.1002/jbm.a.30414; Li, X.M., Feng, Q.L., Cui, F.Z., In vitro degradation of porous nano-hydroxyapatite/collagen/PLLA scaffold reinforced by chitin fibres (2006) Mater Sci Eng C-Biomim Supramol Syst, 26 (4), pp. 716-720. , 1:CAS:528:DC%2BD28XjvFyntr4%3D; Sachlos, E., Gotora, D., Czernuszka, J.T., Collagen scaffolds reinforced with biomimetic composite nano-sized carbonate-substituted hydroxyapatite crystals and shaped by rapid prototyping to contain internal microchannels (2006) Tissue Engineering, 12 (9), pp. 2479-2487. , DOI 10.1089/ten.2006.12.2479; Zhu, X., Eibl, O., Scheideler, L., Geis-Gerstorfer, J., Characterization of nano hydroxyapatite/collagen surfaces and cellular behaviors (2006) Journal of Biomedical Materials Research - Part A, 79 (1), pp. 114-127. , DOI 10.1002/jbm.a.30706; Pieper, J.S., Hafmans, T., Veerkamp, J.H., Van Kuppevelt, T.H., Development of tailor-made collagen-glycosaminoglycan matrices: EDC/NHS crosslinking, and ultrastructural aspects (2000) Biomaterials, 21 (6), pp. 581-593. , DOI 10.1016/S0142-9612(99)00222-7, PII S0142961299002227; Pieper, J.S., Oosterhof, A., Dijkstra, P.J., Veerkamp, J.H., Van Kuppevelt, T.H., Preparation and characterization of porous crosslinked collagenous matrices containing bioavailable chondroitin sulphate (1999) Biomaterials, 20 (9), pp. 847-858. , DOI 10.1016/S0142-9612(98)00240-3, PII S0142961298002403; Pieper, J.S., Van Wachem, P.B., Van Luyn, M.J.A., Brouwer, L.A., Hafmans, T., Veerkamp, J.H., Van Kuppevelt, T.H., Attachment of glycosaminoglycans to collagenous matrices modulates the tissue response in rats (2000) Biomaterials, 21 (16), pp. 1689-1699. , DOI 10.1016/S0142-9612(00)00052-1, PII S0142961200000521; Pieper, J.S., Hafmans, T., Van Wachem, P.B., Van Luyn, M.J.A., Brouwer, L.A., Veerkamp, J.H., Van Kuppevelt, T.H., Loading of collagen-heparan sulfate matrices with bFGF promotes angiogenesis and tissue generation in rats (2002) Journal of Biomedical Materials Research, 62 (2), pp. 185-194. , DOI 10.1002/jbm.10267; Wissink, M.J.B., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H.M., Beugeling, T., Immobilization of heparin to EDC/NHS-crosslinked collagen. Characterization and in vitro evaluation (2001) Biomaterials, 22 (2), pp. 151-163. , 10.1016/S0142-9612(00)00164-2 1:CAS:528:DC%2BD3cXovFGnu7g%3D 11101159; Wissink, M.J.B., Beernink, R., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Improved endothelialization of vascular grafts by local release of growth factor from heparinized collagen matrices (2000) Journal of Controlled Release, 64 (1-3), pp. 103-114. , DOI 10.1016/S0168-3659(99)00145-5, PII S0168365999001455; Wissink, M.J.B., Beernink, R., Scharenborg, N.M., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Endothelial cell seeding of (heparinized) collagen matrices: Effects of bFGF pre-loading on proliferation (after low density seeding) and pro-coagulant factors (2000) Journal of Controlled Release, 67 (2-3), pp. 141-155. , DOI 10.1016/S0168-3659(00)00202-9, PII S0168365900002029; Gcm, S., Yao, C., Prevel, P., Markowicz, M., Schenck, P., Noah, E.M., Modulation of angiogenic potential of collagen matrices by covalent incorporation of heparin and loading with vascular endothelial growth factor (2004) Tissue Eng, pp. 1502-9; Yao, C., Markowicz, M., Pallua, N., Magnus Noah, E., Steffens, G., The effect of cross-linking of collagen matrices on their angiogenic capability (2008) Biomaterials, 29 (1), pp. 66-74. , DOI 10.1016/j.biomaterials.2007.08.049, PII S0142961207007284; Jiao, Y.Y., Ubrich, N., Hoffart, V., Marchand-Arvier, M., Vigneron, C., Hoffman, M., Preparation and characterization of heparin-loaded polymeric microparticles (2002) Drug Dev Ind Pharm, 28 (8), pp. 1033-1041. , 10.1081/DDC-120014740 1:CAS:528:DC%2BD38XnslGnt7c%3D 12378958; Jiao, Y., Ubrich, N., Marchand-Arvier, M., Vigneron, C., Hoffman, M., Lecompte, T., Maincent, P., In vitro and in vivo evaluation of oral heparin-loaded polymeric nanoparticles in rabbits (2002) Circulation, 105 (2), pp. 230-235. , DOI 10.1161/hc0202.101988; Lee, K.W., Yoon, J.J., Lee, J.H., Kim, S.Y., Jung, H.J., Kim, S.J., Joh, J.W., Lee, S.K., Sustained release of vascular endothelial growth factor from calcium-induced alginate hydrogels reinforced by heparin and chitosan (2004) Transplantation Proceedings, 36 (8), pp. 2464-2465. , DOI 10.1016/j.transproceed.2004.08.078, PII S0041134504009480; Schroeder-Tefft, J.A., Bentz, H., Estridge, T.D., Collagen and heparin matrices for growth factor delivery (1997) Journal of Controlled Release, 48 (1), pp. 29-33. , DOI 10.1016/S0168-3659(97)00055-2, PII S0168365997000552; Teixeira, S., Ferraz, M.P., Monteiro, F.J., Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies (2008) J Mater Sci, 19 (2), pp. 855-859. , 1:CAS:528:DC%2BD1cXhs1Wktb8%3D; Edlund, U., Danmark, S., Albertsson, A.-C., A strategy for the covalent functionalization of resorbable polymers with heparin and osteoinductive growth factor (2008) Biomacromolecules, 9 (3), pp. 901-905. , DOI 10.1021/bm701267u; Teixeira, S., Oliveira, S., Ferraz, M., Monteiro, F.J., Three dimensional macroporous calcium phosphates scaffolds for bone tissue engineering (2008) Key Eng Mater Trans Tech, pp. 947-50; Yamamoto, M., Tabata, Y., Hong, L., Miyamoto, S., Hashimoto, N., Ikada, Y., Bone regeneration by transforming growth factor β1 released from a biodegradable hydrogel (2000) Journal of Controlled Release, 64 (1-3), pp. 133-142. , DOI 10.1016/S0168-3659(99)00129-7, PII S0168365999001297; Teixeira, S., Rodriguez, M.A., Pena, P., De Aza, A.H., De Aza, S., Ferraz, M.P., Monteiro, F.J., Physical characterization of hydroxyapatite porous scaffolds for tissue engineering (2009) Mater Sci Eng C, 29 (5), pp. 1510-1514. , 10.1016/j.msec.2008.09.052 1:CAS:528:DC%2BD1MXmtVarurg%3D
Keywords: Achilles Tendon; Animals; Apatite; article; Beneficial effects; Binding and release; Biocompatible Materials; Biological materials; Biomaterials; Bone; Bone and Bones; bone morphogenetic protein 2; Bone morphogenetic proteins; Bone Substitutes; bone tissue; Bone tissue engineering; Bony tissue; Calcium; calcium phosphate; Calcium phosphate crystals; Cattle; Cell attachments; Collagen; collagen degradation; collagen type 1; Collagen type I; controlled study; cross linking; Cross-Linking Reagents; Crosslinking; cyanamide; Degradability; differential scanning calorimetry; Drug delivery; drug delivery system; Durapatite; Grafts; Growth factor; heparin; Hydrogels; hydroxyapatite; Microscopy, Electron, Scanning; n (3 dimethyllaminopropyl) n' ethylcarbodiimide; n hydroxysuccinimide; N-hydroxysuccinimide; Nutrient transport; Peptides; polymer; Polymer replication; Polymers; Polysaccharides; porosity; Porous scaffold; priority journal; protein binding; Scaffolds; Scanning electron microscopy; SEM; Specific time; Structural proteins; Sustained release; Three dimensional; Three-dimensional porous scaffolds; Three-dimensional scaffolds; Tissue engineering; tissue scaffold; Tissue Scaffolds; trinitrobenzenesulfonic acid; unclassified drug; vacuum; Vacuum force

Immobilization of human mesenchymal stem cells within RGD-grafted alginate microspheres and assessment of their angiogenic potential - Bidarra, S.J.; Barrias, C.C.; Barbosa, M.A.; Soares, R.; Granja, P.L. (BiomacromoleculesBiomacromolecules, 2010)
In this work, human mesenchymal stem cells (hMSC) immobilized in RGD-coupled alginate microspheres, with a binary composition of high and low molecular weight alginate, were investigated. Cells immobilized within RGD-alginate microspheres (during 21 days) showed metabolic activity, with an overall viability higher than 90%, short cell extensions, and, when induced, they were able to differentiate into the osteogenic lineage. In osteogenic conditions (comparing to basal conditions), immobilized cells presented alkaline phosphatase (ALP) activity and an upregulation of ALP, collagen type I, and Runx 2 expression. Moreover, mineralization was also detected in immobilized cells under osteogenic stimulus. In addition, it was demonstrated for the first time that MSCs immobilized in this 3D matrix were able to enhance the ability of neighboring endothelial cells to form tubelike structures. Overall, these findings represent a step forward in the development of injectable stem cell carriers for bone tissue engineering. © 2010 American Chemical Society.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm100264aPubMed ID: 20690708Language of Original Document: EnglishCorrespondence Address: Granja, P. L.; INEB-Instituto de Engenharia Biomédica, Rua do Campo Alegre No. 823, 4150-180 Porto, Portugal; email: pgranja@ineb.up.ptMolecular Sequence Numbers: GENBANK: BC021289, NM_000088, NM_002046;Chemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; Alginates; Alkaline Phosphatase, 3.1.3.1; Collagen Type I; DNA Primers; Oligopeptides; arginyl-glycyl-aspartic acid, 99896-85-2References: Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomaterials, 21, pp. 2405-2412;Barralet, J.E., Wang, L., Lawson, M., Triffitt, J.T., Cooper, P.R., Shelton, R.M., Comparison of bone marrow cell growth on 2D and 3D alginate hydrogels (2005) J. Mater. Sci.: Mater. Med., 16, pp. 515-519; Ma, H.L., Hung, S.C., Lin, S.Y., Chen, Y.L., Lo, W.H., Chondrogenesis of human mesenchymal stem cells encapsulated in alginate beads (2003) J. Biomed. Mater. Res., 64, pp. 273-281; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromol. Biosci., 6, pp. 623-633; Smidsrod, O., Skjak-Braek, G., Alginate as immobilization matrix for cells (1990) Trends Biotechnol., 8, pp. 71-78; Jen, A.C., Wake, M.C., Mikos, A.G., Review: Hydrogels for cell immobilization (1996) Biotechnol. Bioeng., 50, pp. 357-364; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Ferreira, M.R.P., Bahia, M.F., Barbosa R. M, A., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability (2008) J. Biomed. Mater. Res. B, 87, pp. 49-8; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.-J., Barrias, C.C., Salema, R., Granja, P.L., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28, pp. 3644-3655; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24, pp. 4023-4029; Grellier, M., Granja, P.L., Fricain, J.-C., Bidarra, S.J., Renard, M., Bareille, R., Bourget, C., Barbosa, M.A., The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect (2009) Biomaterials, 30, pp. 3271-3278; Caplan, A.I., Adult mesenchymal stem cells for tissue engineering versus regenerative medicine (2007) J. Cell. Physiol., 213, pp. 341-347; Horwitz, E.M., MSC: A coming of age in regenerative medicine (2006) Cytotherapy, 8, pp. 194-195; Sumanasinghe, R.D., Bernacki, S.H., Loboa, E.G., Osteogenic differentiation of human mesenchymal stem cells in collagen matrices: Effect of uniaxial cyclic tensile strain on bone morphogenetic protein (BMP-2) mRNA expression (2006) Tissue Eng., 12, pp. 3459-3465; Granero-Molto, F., Weis, J.A., Longobardi, L., Spagnoli, A., Role of mesenchymal stem cells in regenerative medicine: Application to bone and cartilage repair (2008) Expert Opin. Biol. Ther., 8, pp. 255-268; Markusen, J.F., Mason, C., Hull, D.A., Town, M.A., Tabor, A.B., Clements, M., Boshoff, C.H., Dunnill, P., Behavior of adult human mesenchymal stem cells entrapped in alginate-GRGDY beads (2006) Tissue Eng., 12, pp. 821-830; Duggal, S., Fronsdal, K.B., Szoke, K., Shahdadfar, A., Melvik, J.E., Brinchmann, J.E., Phenotype and gene expression of human mesenchymal stem cells in alginate scaffolds (2009) Tissue Eng., Part A, 15, pp. 1763-1773; Kasper, G., Dankert, N., Tuischer, J., Hoeft, M., Gaber, T., Glaeser, J.D., Zander, D., Duda, G.N., Mesenchymal stem cells regulate angiogenesis according to their mechanical environment (2007) Stem Cells, 25, pp. 903-910; Gruber, R., Kandler, B., Holzmann, P., Vogele-Kadletz, M., Losert, U., Fischer, M.B., Watzek, G., Bone marrow stromal cells can provide a local environment that favors migration and formation of tubular structures of endothelial cells (2005) Tissue Eng., 11, pp. 896-903; Valarmathi, M.T., Yost, M.J., Goodwin, R.L., Potts, J.D., A three-dimensional tubular scaffold that modulates the osteogenic and vasculogenic differentiation of rat bone marrow stromal cells (2008) Tissue Eng., Part A, 14, pp. 491-504; Potapova, I.A., Gaudette, G.R., Brink, P.R., Robinson, R.B., Rosen, M.R., Cohen, I.S., Doronin, S.V., Mesenchymal stem cells support migration, extracellular matrix invasion, proliferation, and survival of endothelial cells in vitro (2007) Stem Cells, 25, pp. 1761-1768; Moon, J.J., West, J.L., Vascularization of engineered tissues: Approaches to promote angiogenesis in biomaterials (2008) Curr. Top. Med. Chem., 8, pp. 300-310; Carano, R.A.D., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discovery Today, 8, pp. 980-989; Eriksen, E.F., Eghbali-Fatourechi, G.Z., Khosla, S., Remodeling and vascular spaces in bone (2007) J. Bone Miner. Res., 22, pp. 1-6; Schroeder, T.M., Jensen, E.D., Westendorf, J.J., Runx2: A master organizer of gene transcription in developing and maturing osteoblasts (2005) Birth Defects Res., Part C, 75, pp. 213-225; Soares, R., Guo, S., Ga'rtner, F., Schmitt, F., Russo, J., 17β-Estradiol-mediated vessel assembly and stabilization in tumor angiogenesis requires TGFβ and EGFR crosstalk (2003) Angiogenesis, 6, pp. 271-281; Kubota, Y., Kleinman, H.K., Martin, G.R., Lawley, T.J., Role of laminin and basement membrane in the morphological differentiation of human endothelial cells into capillary-like structures (1988) J. Cell Biol., 107, pp. 1589-1598; Kaully, T., Kaufman-Francis, K., Lesman, A., Levenberg, S., Vascularization-The conduit to viable engineered tissues (2009) Tissue Eng., Part B, 15, pp. 159-169; Silva, E.A., Mooney, D.J., Spatiotemporal control of vascular endothelial growth factor delivery from injectable hydrogels enhances angiogenesis (2007) J. Thromb. Haemost., 5, pp. 590-598; Fuchs, S., Jiang, X., Schmidt, H., Dohle, E., Ghanaati, S., Orth, C., Hofmann, A., Kirkpatrick, C.J., Dynamic processes involved in the pre-vascularization of silk fibroin constructs for bone regeneration using outgrowth endothelial cells (2009) Biomaterials, 30, pp. 1329-1338; Hsiong, S.X., Mooney, D.J., Regeneration of vascularized bone (2006) Periodontol. 2000, 41, pp. 109-122; Abbah, S., Lu, W., Chan, D., Cheung, K., Liu, W., Zhao, F., Li, Z., Luk, K., Osteogenic behavior of alginate encapsulated bone marrow stromal cells: An in vitro study (2008) J. Mater. Sci.: Mater. Med., 19, pp. 2113-2119; Moioli, E.K., Hong, L., Mao, J.J., Inhibition of osteogenic differentiation of human mesenchymal stem cells (2007) Wound Repair Regen., 15, pp. 413-421; Healy, K.E., Guldberg, R.E., Bone tissue engineering (2007) J. Musculoskelet. Neuronal Interact., 7, pp. 328-330; Stein, G.S., Lian, J.B., Owen, T.A., Relationship of cell growth to the regulation of tissue-specific gene expression during osteoblast differentiation (1990) FASEB J., 4, pp. 3111-3123; Lian, J.B., Stein, G.S., Concepts of osteoblast growth and differentiation: Basis for modulation of bone cell development and tissue formation (1992) Crit. Rev. Oral Biol. Med., 3, pp. 269-305; Huang, Y.-C., Kaigler, D., Rice, K.G., Krebsbach, P.H., Mooney, D.J., Combined angiogenic and osteogenic factor delivery enhances bone marrow stromal cell-driven bone regeneration (2005) J. Bone Miner. Res., 20, pp. 848-857; Fang, T.D., Salim, A., Xia, W., Nacamuli, R.P., Guccione, S., Song, H.M., Carano, R.A., Longaker, M.T., Angiogenesis is required for successful bone induction during distraction osteogenesis (2005) J. Bone Miner. Res., 20, pp. 1114-1124; Villars, F., Bordenave, L., Bareille, R., Amédée, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: Role of VEGF (2000) J. Cell. Biochem., 79, pp. 672-685; Kaigler, D., Krebsbach, P.H., Polverini, P.J., Mooney, D.J., Role of vascular endothelial growth factor in bone marrow stromal cell modulation of endothelial cells (2003) Tissue Eng., 9, pp. 95-103; Grellier, M., Ferreira-Tojais, N., Bourget, C., Bareillke, R., Guillemot, F., Amédée, J., Role of vascular endothelial growth factor in the communication between human osteoprogenitors and endothelial cells (2009) J. Cell. Biochem., 106, pp. 390-398; Yu, J., Gu, Y., Du, K.T., Mihardja, S., Sievers, R.E., Lee, R.J., The effect of injected RGD modified alginate on angiogenesis and left ventricular function in a chronic rat infarct model (2009) Biomaterials, 30, pp. 751-756
Keywords: Alginate; Alginates; alginic acid; alkaline phosphatase; Alkaline phosphatase activity; angiogenesis; arginylglycylaspartic acid; article; Basal conditions; Base Sequence; Binary composition; bone development; Bone tissue engineering; Cell culture; cell differentiation; Cell extension; Cell immobilization; cell metabolism; cell structure; cell viability; collagen type 1; Collagen type I; controlled study; DNA Primers; Endothelial Cells; endothelium cell; enzyme activity; human; human cell; Human mesenchymal stem cells; Humans; immobilized cell; Immobilized cells; Low molecular weight; matrix; Mesenchymal stem cell; Mesenchymal Stem Cells; Metabolic activity; Microscopy, Electron, Scanning; microsphere; Microspheres; molecular weight; Neovascularization, Physiologic; nucleotide sequence; Oligopeptides; osteoblast; Osteogenic; Phosphatases; priority journal; protein expression; quantitative analysis; Reverse Transcriptase Polymerase Chain Reaction; stem cell; Stem cells; three dimensional imaging; Tissue engineering; transcription factor RUNX2; umbilical vein; Up-regulation; upregulation

An improved collagen scaffold for skeletal regeneration - Oliveira, S.M.; Ringshia, R.A.; Legeros, R.Z.; Clark, E.; Yost, M.J.; Terracio, L.; Teixeira, C.C. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
Bone repair and regeneration is one of the most extensively studied areas in the field of tissue engineering. All of the current tissue engineering approaches to create bone focus on intramembranous ossification, ignoring the other mechanism of bone formation, endochondral ossification. We propose to create a transient cartilage template in vitro, which could serve as an intermediate for bone formation by the endochondral mechanism once implanted in vivo. The goals of the study are (1) to prepare and characterize type I collagen sponges as a scaffold for the cartilage template, and (2) to establish a method of culturing chondrocytes in type I collagen sponges and induce cell maturation. Collagen sponges were generated from a 1% solution of type I collagen using a freeze/dry technique followed by UV light crosslinking. Chondrocytes isolated from two locations in chick embryo sterna were cultured in these sponges and treated with retinoic acid to induce chondrocyte maturation and extracellular matrix deposition. Material strength testing as well as microscopic and biochemical analyzes were conducted to evaluate the properties of sponges and cell behavior during the culture period. We found that our collagen sponges presented improved stiffness and supported chondrocyte attachment and proliferation. Cells underwent maturation, depositing an abundant extracellular matrix throughout the scaffold, expressing high levels of type X collagen, type I collagen and alkaline phosphatase. These results demonstrate that we have created a transient cartilage template with potential to direct endochondral bone formation after implantation. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32694PubMed ID: 20186736Language of Original Document: EnglishCorrespondence Address: Teixeira, C. C.; Department of Basic Science and Craniofacial Biology, Department of Biomaterials and Biomimetics, New York University College of Dentistry, New York, NY 10010, United States; email: ct40@nyu.eduChemicals/CAS: alkaline phosphatase, 9001-78-9; retinoic acid, 302-79-4; Biocompatible Materials; Collagen, 9007-34-5; Protein IsoformsReferences: Pountos, I., Jones, E., Tzioupis, C., Mcgonagle, D., Giannoudis, P.V., Growing bone and cartilage. The role of mesenchymal stem cells (2006) J Bone Joint Surg Br, 88, pp. 421-426;Newman, A.P., Articular cartilage repair (1998) Am J Sports Med, 26, pp. 309-324; Tomihisa, K., Tomoo, M., Toshitaka, T., Tomoyuki, S., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; Weiss, P., Layrolle, P., Clergeau, L.P., Enckel, B., Pilet, P., Amouriq, Y., Daculsi, G., Giumelli, B., The safety and efficacy of an injectable bone substitute in dental sockets demonstrated in a human clinical trial (2007) Biomaterials, 28, pp. 3295-3305; Verlaan, J.J., Oner, F.C., Dhert, W.J., Anterior spinal column augmentation with injectable bone cements (2006) Biomaterials, 27, pp. 290-301; Zelzer, E., Olsen, B.R., The genetic basis for skeletal diseases (2003) Nature, 423, pp. 343-348; Ivaska, K.K., Gerdhem, P., Åkesson, K., Garnero, P., Obrant, K.J., Effect of fracture on bone turnover markers: A longitudinal study comparing marker levels before and after injury in 113 elderly women (2007) J Bone Miner Res, 22, pp. 1155-1164; Hunziker, E.B., Articular cartilage repair: Basic science and clinical progress. A review of the current status and prospects (2002) Osteoarthritis Cartilage, 10, pp. 432-463; Curran, S.J., Chen, R., Curran, J.M., Hunt, J.A., Expansion of human chondrocytes in an intermittent stirred flow bioreactor, using modified biodegradable microspheres (2005) Tissue Eng, 11, pp. 1312-1322; Vinatier, C., Magne, D., Moreau, A., Gauthier, O., Malard, O., Vignes-Colombeix, C., Daculsi, G., Guicheux, J., Engineering cartilage with human nasal chondrocytes and a silanized hydroxypropyl methylcellulose hydrogel (2007) J Biomed Mater Res Part A, 80, pp. 66-74; Pound, J.C., Green, D.W., Chaudhuri, J.B., Mann, S., Roach, H.I., Oreffo, R.O., Strategies to promote chondrogenesis and osteogenesis from human bone marrow cells and articular chondrocytes encapsulated in polysaccharide templates (2006) Tissue Eng, 12, pp. 2789-2799; Kasten, P., Vogel, J., Luginbuhl, R., Niemeyer, P., Tonak, M., Lorenz, H., Helbig, L., Leo, A., Ectopic bone formation associated with mesenchymal stem cells in a resorbable calcium deficient hydroxyapatite carrier (2005) Biomaterials, 26, pp. 5879-5889; Joon Yung, L., Musgrave, D., Pelinkovic, D., Fukushima, K., Cummins, J., Usas, A., Robbins, P., Huard, J., Effect of bone morphogenetic protein-2-expressing muscle-derived cells on healing of critical-sized bone defects in mice (2001) Journal of Bone and Joint Surgery - Series a, 83 (7), pp. 1032-1039; Sumanasinghe, R.D., Osborne, J.A., Loboa, E.G., Mesenchymal stem cell-seeded collagen matrices for bone repair: Effects of cyclic tensile strain, cell density, and media conditions on matrix contraction in vitro (2008) J Biomed Mater Res Part A, 88, pp. 778-786; Alsberg, E., Anderson, K.W., Albeiruti, A., Rowley, J.A., Mooney, D.J., Engineering growing tissues (2002) Proc Natl Acad Sci USA, 99, pp. 12025-12030; Arpornmaeklong, P., Suwatwirote, N., Pripatnanont, P., Oungbho, K., Growth and differentiation of mouse osteoblasts on chitosan-collagen sponges (2007) Int J Oral Maxillacial Surgery, 36, pp. 328-337; Lode, A., Bernhardt, A., Gelinsky, M., Cultivation of human bone marrow stromal cells on three-dimensional scaffolds of mineralized collagen: Influence of seeding density on colonization, proliferation and osteogenic differentiation (2008) J Tissue Eng Regenerative Med, 2, pp. 400-407; Balooch, M., Habelitz, S., Kinney, J.H., Marshall, S.J., Marshall, G.W., Mechanical properties of mineralized collagen fibrils as influenced by demineralization (2008) J Struct Biol, 162, pp. 404-410; Gelse, K., Poschl, E., Aigner, T., Collagens-structure, function, and biosynthesis (2003) Adv Drug Deliv Rev, 55, pp. 1531-1546; Berglund, J.D., Mohseni, M.M., Nerem, R.M., Sambanis, A., A biological hybrid model for collagen-based tissue engineered vascular constructs (2003) Biomaterials, 24, pp. 1241-1254; Chvapil, M., Collagen sponge: Theory and practice of medical applications (1977) J Biomed Mater Res, 11, pp. 721-741; Chvapil, M., Kronenthal, L., Van Winkle, W., Medical and surgical applications of collagen (1973) Int Rev Connect Tissue Res, 6, pp. 1-61; Matton, G., Anseeuw, A., De Keyser, F., The history of injectable biomaterials and the biology of collagen (1985) Aesthetic Plastic Surgery, 9 (2), pp. 133-140. , DOI 10.1007/BF01570345; Radhika, M., Babu, M., Sehgal, P.K., Cellular proliferation on desamidated collagen matrices (1999) Comp Biochem Physiol C Pharmacol Toxicol Endocrinol, 124, pp. 131-139; Elliott, J.T., Woodward, J.T., Langenbach, K.J., Tona, A., Jones, P.L., Plant, A.L., Vascular smooth muscle cell response on thin films of collagen (2005) Matrix Biol, 24, pp. 489-502; Song, J., Rolfe, B.E., Hayward, I.P., Campbell, G.R., Campbell, J.H., Effects of collagen gel configuration on behavior of vascular smooth muscle cells in vitro: Association with vascular morphogenesis (2000) In Vitro Cell Dev Biol Anim, 36, pp. 600-610; Weinberg, C.B., Bell, E., A blood vessel model constructed from collagen and cultured vascular cells (1986) Science, 231 (4736), pp. 397-400; Reid, G.G., Gorham, S.D., Lackie, J.M., The attachment, spreading and growth of baby hamster-kidney cells on collagen, chemically modified collagen and collagen-composite substrata (1993) J Mater Sci-Mater Med, 4, pp. 201-209; Michalopoulos, G., Pitot, H.C., Primary culture of parenchymal liver cells on collagen membranes. Morphological and biochemical observations (1975) Exp Cell Res, 94, pp. 70-78; Winder, S.J., Turvey, A., Forsyth, I.A., Characteristics of ruminant mammary epithelial cells grown in primary culture in serumfree medium (1992) J Dairy Res, 59, pp. 491-498; Sato, T., Chen, G., Ushida, T., Ishii, T., Ochiai, N., Tateishi, T., Tissue-engineered cartilage by in vivo culturing of chondrocytes in PLGA-collagen hybrid sponge (2001) Mater Sci Engineering: C, 17, pp. 83-89; Takahiro, O., Keizo, T., Yosuke, H., Takashi, U., Tamotsu, T., Tetsuya, T., Effect of type I and type II collagen sponges as 3D scaffolds for hyaline cartilage-like tissue regeneration on phenotypic control of seeded chondrocytes in vitro (2004) Mater Sci Eng C, 24, pp. 407-411; Fuchs, J.R., Kaviani, A., Oh, J.T., Lavan, D., Udagawa, T., Jennings, R.W., Wilson, J.M., Fauza, D.O., Diaphragmatic reconstruction with autologous tendon engineered from mesenchymal amniocytes (2004) J Pediatr Surg, 39, pp. 834-838; Kall, S., Nöth, U., Reimers, K., Choi, C.Y.U., Muehlberger, T., Allmeling, C., Jahn, S., Vogt, P.M., In vitro fabrication of tendon substitutes using human mesenchymal stem cells and a collagen type i gel (2004) Handchir Mikrochir Plast Chir, 4, pp. 205-211; Domaschke, H., Gelinsky, M., Burmeister, B., Fleig, R., Hanke, T., Reinstorf, A., Pompe, W., Rosen-Wolff, A., In vitro ossification and remodeling of mineralized collagen i scaffolds (2006) Tissue Eng, 12, pp. 949-958; Rodrigues, C.V.M., Serricella, P., Linhares, A.B.R., Guerdes, R.M., Borojevic, R., Rossi, M.A., Duarte, M.E.L., Farina, M., Characterization of a bovine collagen-hydroxyapatite composite scaffold for bone tissue engineering (2003) Biomaterials, 24, pp. 4987-4997; Cooperman, L., Michaeli, D., The immunogenicity of injectable collagen. I. A 1-year prospective study (1984) J Am Acad Dermatol, 10, pp. 638-646; Delustro, F., Condell, R.A., Nguyen, M.A., Mcpherson, J.M., A comparative study of the biologic and immunologic response to medical devices derived from dermal collagen (1986) J Biomed Mater Res, 20, pp. 109-120; Sandberg, M., Vurio, E., Localization of types I, II, and III collagen mRNAs in developing human skeletal tissues by in situ hybridization (1987) J Cell Biol, 104, pp. 1077-1084; DeLustro, F., Smith, S.T., Sundsmo, J., Reaction to injectable collagen: Results in animal models and clinical use (1987) Plastic and Reconstructive Surgery, 79 (4), pp. 581-592; Lynn, A.K., Yannas, I.V., Bonfield, W., Antigenicity and immunogenicity of collagen (2004) J Biomed Mater Res Part B: Appl Biomaterials, 71, pp. 343-354; Mizuno, M., Shindo, M., Kobayashi, D., Tsuruga, E., Amemiya, A., Kuboki, Y., Osteogenesis by bone marrow stromal cells maintained on type I collagen matrix gels in vivo (1997) Bone, 20, pp. 101-107; Wambach, B.A., Cheung, H., Josephson, G.D., Cartilage tissue engineering using thyroid chondrocytes on a type i collagen matrix (2000) Laryngoscope, 110, pp. 2008-2011; Rajpurohit, R., Koch, C.J., Tao, Z., Teixeira, C.M., Shapiro, I.M., Adaptation of chondrocytes to low oxygen tension: Relationship between hypoxia and cellular metabolism (1996) J Cell Physiol, 168, pp. 424-432; Schipani, E., Ryan, H.E., Didrickson, S., Kobayashi, T., Knight, M., Johnson, R.S., Hypoxia in cartilage: HIF-1 alpha is essential for chondrocyte growth arrest and survival (2001) Genes Dev, 15, pp. 2865-2876; Maes, C., Carmeliet, P., Moermans, K., Stockmans, I., Smets, N., Collen, D., Bouillon, R., Carmeliet, G., Impaired angiogenesis and endochondral bone formation in mice lacking the vascular endothelial growth factor isoforms VEGF164 and VEGF188 (2002) Mech Dev, 111, pp. 61-73; Petersen, W., Tsokos, M., Pufe, T., Expression of VEGF121 and VEGF165 in hypertrophic chondrocytes of the human growth plate and epiphyseal cartilage (2002) J Anat, 201, pp. 153-157; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: In vitro studies (2009) Tissue Eng, 15, pp. 625-634; Teixeira, C.C., Nemelivsky, Y., Karkia, C., Legeros, R.Z., Biphasic calcium phosphate: A scaffold for growth plate chondrocyte maturation (2006) Tissue Eng, 12, pp. 2283-2289; Oliveira, S.M., Turner, G., Mijares, D., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: In vivo studies (2009) Tissue Eng, 15, pp. 635-643; Hiraoka, Y., Kimura, Y., Ueda, H., Tabata, Y., Fabrication and biocompatibility of collagen sponge reinforced with poly(glycolic acid) fiber (2003) Tissue Eng, 9, pp. 1101-1112; Yost, M.J., Baicu, C.F., Stonerock, C.E., Terracio, L., A novel tubular scaffold for cardiovascular tissue engineering (2004) Tissue Eng, 10, pp. 273-284; Mow, V.C., Kuei, S.C., Lai, W.M., Armstrong, C.G., Biphasic creep and stress relaxation of articular cartilage in compression? Theory and experiments (1980) J Biomech Eng, 102, pp. 73-84; Iwamoto, M., Shapiro, I.M., Yagami, K., Boskey, A.L., Leboy, P.S., Adams, S.L., Pacifici, M., Retinoic acid induces rapid mineralization and expression of mineralization-related genes in chondrocytes (1993) Exp Cell Res, 207, pp. 413-420; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein content, and alkaline phosphatase activity of chondrocyte cultures (1995) Calcif Tissue Int, 56, pp. 252-256; Leboy, P.S., Vaias, L., Uschmann, B., Golub, E., Adams, S.L., Pacifici, M., Ascorbic acid induces alkaline phosphatase, type X collagen, and calcium deposition in cultured chick chondrocytes (1989) Journal of Biological Chemistry, 264 (29), pp. 17281-17286; Whyte, M.P., Hypophosphatasia and the role of alkaline phosphatase in skeletal mineralization (1994) Endocr Rev, 15, pp. 439-461; Wang, W., Kirsch, T., Retinoic acid stimulates annexin-mediated growth plate chondrocyte mineralization (2002) J Cell Biol, 157, pp. 1061-1069; Chen, D., Zhao, M., Mundy, G.R., Bone morphogenetic proteins (2004) Growth Factors, 22, pp. 233-241; Gerstenfeld, L.C., Shapiro, F.D., Expression of bone-specific genes by hypertrophic chondrocytes: Implications of the complex functions of the hypertrophic chondrocyte during endochondral bone development (1996) J Cell Biochem, 62, pp. 1-9; Bianco, P., Cancedda, F.D., Riminucci, M., Cancedda, R., Bone formation via cartilage models: The "borderline" chondrocyte (1998) Matrix Biol, 17, pp. 185-192; De Bernard, B., Bianco, P., Bonucci, E., Costantini, M., Lunazzi, G.C., Martinuzzi, P., Modricky, C., Pollesello, P., Biochemical and immunohistochemical evidence that in cartilage an alkaline phosphatase is a Ca 2" - Binding glycoprotein (1986) J Cell Biol, 103, pp. 1615-1623; Galotto, M., Campanile, G., Robino, G., Cancedda, F.D., Bianco, P., Cancedda, R., Hypertrophic chondrocytes undergo further differentiation to osteoblast- Like cells and participate in the initial bone formation in developing chick embryo (1994) Journal of Bone and Mineral Research, 9 (8), pp. 1239-1249; Mark, M.P., Butler, W.T., Prince, C.W., Finkelman, R.D., Ruch, J.V., Developmental expression of 44-kDa bone phosphoprotein (osteopontin) and bone gamma-carboxyglutamic acid (Gla)-containing protein (osteocalcin) in calcifying tissues of rat (1988) Differentiation, 37, pp. 123-136; Sims, C.D., Butler, P.E., Casanova, R., Lee, B.T., Randolph, M.A., Lee, W.P., Vacanti, C.A., Yaremchuk, M.J., Injectable cartilage using polyethylene oxide polymer substrates (1996) Plast Reconstr Surg, 98, pp. 843-850; Woodard, J.C., Donovan, G.A., Fisher, L.W., Pathogenesis of vitamin (A and D)-induced premature growth-plate closure in calves (1997) Bone, 27, pp. 171-182; Liao, E., Yaszemski, M., Krebsbach, P., Hollister, S., Tissue-engineered cartilage constructs using composite hyaluronic acid/ collagen I hydrogels and designed poly(propylene fumarate) scaffolds (2007) Tissue Eng, 13, pp. 537-550; Gerstenfeld, L.C., Cruceta, J., Shea, C.M., Sampath, K., Barnes, G.L., Einhorn, T.A., Chondrocytes provide morphogenic signals that selectively induce osteogenic differentiation of mesenchymal stem cells (2002) Journal of Bone and Mineral Research, 17 (2), pp. 221-230
Keywords: alkaline phosphatase; animal cell; animal tissue; Animals; article; Biocompatible Materials; Body fluids; Bone; Bone and Bones; Bone Regeneration; Cartilage; cartilage cell; Cattle; Cell culture; cell maturation; chick embryo; Chondrocytes; Collagen; collagen implant; collagen type 1; collagen type 10; Compressive Strength; controlled study; embryo; enchondral ossification; Endochondral ossification; extracellular matrix; freeze drying; Humans; immunohistochemistry; Ligaments; materials testing; Microscopy, Electron, Scanning; nonhuman; Phosphatases; protein cross linking; Protein Isoforms; retinoic acid; Scaffolds; Scanning electron microscopy; Stress, Mechanical; Tissue engineering; tissue scaffold; Type I collagen; Type X collagen; Ultraviolet radiation

In vitro study of the proliferation and growth of human bone marrow cells on apatite-wollastonite-2M glass ceramics - Magallanes-Perdomo, M.; De Aza, A.H.; Mateus, A.Y.; Teixeira, S.; Monteiro, F.J.; De Aza, S.; Pena, P. (Acta BiomaterialiaActa Biomater., 2010)
This study concerns the preparation and in vitro characterization of an apatite-wollastonite-2M bioactive glass ceramic which is intended to be used for the regeneration of hard tissue (i.e. in dental and craniomaxillofacial surgery). This bioglass ceramic has been obtained by appropriate thermal treatment through the devitrification (crystallization) of a glass with a stoichiometric eutectic composition within the Ca 3(PO 4)2-CaSiO 3 binary system. Crack-free specimens of the bioglass ceramic were immersed in human bone marrow cell cultures for 3, 7, 14 and 21 days, in order to study biocompatibility. Cell morphology, proliferation and colonization were assessed by scanning electron microscopy and confocal laser scanning microscopy. A total protein content assay was used to evaluate the viability and proliferation of cultured bone marrow cells. The results showed that the cells were able to adhere and proliferate on the designed material due to the essentiality of silicon and calcium as accessory factors for cell activity stimulation. © 2009 Acta Materialia Inc. All rights reserved.
Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.12.027Language of Original Document: EnglishCorrespondence Address: De Aza, A. H.; Instituto de Cerámica y Vidrio, CSIC, C/Kelsen 5, 28049 Madrid, Spain; email: aaza@icv.csic.esChemicals/CAS: apatite, 64476-38-6; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; calcium silicate, 1344-95-2, 13983-17-0; silicate, 12627-13-3; Apatites; Bone Substitutes; Calcium Compounds; Ceramics; Silicates; calcium silicate, 1344-95-2References: Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, , London: World Scientific;Hench, L.L., Bioceramics: From concept to clinic (1991) J. Am. Ceram. Soc., 74, pp. 1487-1510; Best, S.M., Porter, A.E., Thian, E.S., Huan, J., Bioceramics: Past, present and for the future (2008) J. Eur. Ceram. Soc., 28, pp. 1319-1327; Chevalier, J., Gremillard, L., Ceramics for medical applications: A picture for the next 20 years (2009) J. Eur. Ceram. Soc., 29, pp. 1245-1255; Teixeira, S., Oliveira, S., Ferraz, M.P., Monteiro, F.J., Mesenchymal stem cell proliferation and morphological analysis on interconnected macroporous structures (2007) Key Eng. Mater., 330-332, pp. 1129-1132; Temenoff, J.S., Mikos, A.G., (2008) Biomaterials: The Intersection of Biology and Materials Science, p. 471. , London: Pearson International; Carlisle, E.M., Biochemical and morphological changes associated with long bone abnormalities in silicon deficiency (1980) J. Nutr., 110, pp. 1046-1055; Carlisle, E.M., A silicon requirement for normal skull formation (1980) J. Nutr., 110, pp. 352-359; Reffitt, M., Ogston, N., Jugdaohsingh, R., Cheung, H.F., Evans, B.A., Thompson, R.P., Orthosilicic acid stimulates collagen type 1 synthesis and osteoblastic differentiation in human osteoblast-like cells in vitro (2003) Bone, 32, pp. 127-135; Brown, L., Luklinska, Z., De Aza, P.N., De Aza, S., Anseau, M., Hughes, F.J., Mechanism of osteoinduction by pseudowollastonite (psW) ceramic (2004) 7th World Biomaterials Congress, , Paper presented at the, Sydney; De Aza, P.N., De Aza, A.H., De Aza, S., Crystalline bioceramic materials (2005) Bol Soc. Esp. Ceram. V, 44, pp. 135-145; De Aza, P.N., De Aza, A.H., Pena, P., De Aza, S., Bioactive glasses and glass-ceramics (2007) Bol Soc. Esp. Ceram. V, 46, pp. 45-55; Kokubo, T., Ito, S., Sakka, S., Formation of a high-strength bioactive glass-ceramic in the system MgO-CaO-SiO 2-P 2O 5 (1986) J. Mat. Sci., 21, pp. 536-540; De Aza, P.N., Guitián, F., De Aza, S., Bioeutectic: A new ceramic material for human bone replacement (1997) Biomaterials, 18, pp. 1285-1291; De Aza, P.N., Guitián, F., De Aza, S., A new bioactive material which transforms in situ into hydroxyapatite (1998) Act Mater., 46, pp. 2541-2549; De Aza, P.N., Guitián, F., De Aza, S., Bioeutectics (1994) Internacional Trademark, 780 (1), p. 697. , Universidad de Santiago de Compostela; De Aza, P.N., Guitián, F., De Aza, S., Bioeutectics: New bioceramic materials (1999) Advances in Science and Technology, 28, pp. 25-32. , Vicenzini P, editor, Materials in clinical applications, Faenza: Publi Techna Italia; De Aza, P.N., Luklinska, Z.B., Anseau, M.R., Guitian, F., De Aza, S., Reactivity of wollastonite-tricalcium phosphate ceramic (Bioeutectic ®) in parotid human saliva (2000) Biomaterials, 21, pp. 1735-1741; De Aza, A.H., Velasquez, P., Alemany, M.I., Pena, P., De Aza, P.N., In situ bone-like apatite formation from a Bioeutectic ceramic in SBF dynamic flow (2007) J. Am. Ceram. Soc., 90, pp. 1200-1207; Sánchez, F.M., Díaz-Güemes, I., Enciso, S., Moreno, B., De Aza, A.H., Carrodeguas, R.G., Evaluación de una cerámica bioactiva de p-wollastonita como sustituto óseo en el modelo ovino (2009) XVII Congreso Internacional de la Sociedad Española de Cirugía Veterinaria, , Cáceres; 6-8 November, Paper Presented at the; Llorca, J., Orera, V., Directionally solidified eutectic ceramic oxides (2006) Prog. Mater. Sci., 51, pp. 711-809; Magallanes-Perdomo, M., Carrodeguas, R.G., Pena, P., De Aza, P.N., De Aza, S., De Aza, A.H., Non-isothermal devitrification study of wollastonite-tricalcium phosphate Bioeutectic ® glass (2009) Key Eng. Mat., 396-398, pp. 127-130; Magallanes-Perdomo, M., Pena, P., De Aza, P.N., Carrodeguas, R.G., Rodriguez, M.A., Turrillas, X., Devitrification studies of wollastonite-tricalcium phosphate eutectic glass (2009) Acta Biomater, 5, pp. 3057-3066; De Aza, P.N., Guitián, F., De Aza, S., Phase diagram of wollastonite-tricalcium phosphate (1995) J. Am. Ceram. Soc., 78, pp. 1653-1656; Young, R.A., (1993) The Rietveld Method, p. 336. , Oxford: Oxford University Press; Larson, A.C., Von Dreele, R.B., (1994) Los Alamos National Laboratory Report No. LA-UR-86-748, , Los Alamos, NM: Los Alamos National Laboratory; Finger, L.W., Cox, D.E., Jephcoat, A.P., A correction for powder diffraction peak asymmetry due to axial divergence (1994) J. Appl. Cryst., 27, pp. 892-900; Wilson, R.M., Elliott, J.C., Dowker, S.E., Rodriguez-Lorenzo, L.M., Rietveld refinements and spectroscopic studies of the structure of Ca-deficient apatite (2005) Biomaterials, 26, pp. 1317-1327; Wilson, R.M., Elliott, J.C., Dowker, S.E., Rodriguez-Lorenzo, L.M., Ca 9.303 (PO 4) 6 (OH) 0.6061.97 (H 2O) (2005) ICSD Collection Code 152190, Inorganic Crystal Structure Database, , Karlsruhe: Fachonformationszentrum; Trojer, F.J., The crystal structure of parawollastonite (1968) Zeitschrift fur Kristallographie Kristallgeometrie Kristallphysik Kristallchemie, 127, pp. 291-308; Trojer, F.J., CaSiO 3-wollastonite-2M (1968) ICSD Collection Code 34908, Inorganic Crystal Structure Database, , Karlsruhe: Fachonformationszentrum; De La, T.A.G., Bruque, S., Aranda, M.A.G., Rietveld quantitative amorphous content analysis (2001) J. Appl. Cryst., 34, pp. 196-202; De Aza, A.H., De La Torre, A.G., Aranda, M.A.G., Valle, F.J., De Aza, S., Rietveld quantitative analysis of Buen Retiro porcelains (2004) J. Am. Ceram. Soc., 87, pp. 449-454; Magallanes-Perdomo, M., Luklinska, Z.B., De Aza, A.H., Carrodeguas, R.G., De Aza, S., Pena, P., Bone like apatite forming ability of apatite-wollastonite glass ceramic (2009) 11th International Conference and Exhibition of the European Ceramic Society, , Krakow, Poland; 21-25 June, Paper Presented at the; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and double-layer HA-P 2O 3/CaO glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behavior (2001) J. Mater. Sci. Mater. Med., 12, pp. 629-638; Meseguer-Olmo, L., Bernabeu-Esclapez, A., Ros-Martinez, E., Sanchez-Salcedo, S., Padilla, S., Martin, A.I., In vitro behaviour of adult mesenchymal stem cells seeded on a bioactive glass ceramic in the SiO 2-CaO-P 2O 5 system (2008) Acta Biomater, 4, pp. 1104-1113; Muller, P., Bulnheim, U., Diener, A., Luthen, F., Teller, M., Klinkenberg, E.D., Calcium phosphate surfaces promote osteogenic differentiation of mesenchymal stem cells (2008) J. Cell. Mol. Med., 12, pp. 281-291; Saldana, L., Sanchez-Salcedo, S., Izquierdo-Barba, I., Bensiamar, F., Munuera, L., Vallet-Regi, M., Calcium phosphate-based particles influence osteogenic maturation of human mesenchymal stem cells (2009) Acta Biomater, 5, pp. 1294-1305; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Effect of titanium surface-roughness on proliferation, differentiation, and protein-synthesis of human osteoblast-like cells (MG63) (1995) J. Biomed. Mater. Res., 29, pp. 389-401; Bowers, K.T., Keller, J.C., Randolph, B.A., Wick, D.G., Michaels, C.M., Optimization of surface micromorphology for enhanced osteoblast responses in vitro (1992) Int. J. Oral. Maxillofac. Implants, 7, pp. 302-310; Boyan, B.D., Batzer, R., Kieswetter, K., Liu, Y., Cochran, D.L., Szmuckler-Moncler, S., Titanium surface roughness alters responsiveness of MG63 osteoblastlike cells to 1 alpha, 25-(OH) (2) D-3 (1998) J. Biomed. Mater. Res., 39, pp. 77-85; Mateus, A.Y.P., Barrias, C.C., Ribeiro, C., Ferraz, M.P., Monteiro, F.J., Comparative study of nanohydroxyapatite microspheres for medical applications (2008) J. Biomed. Mater. Res. A, 86, pp. 483-493; Ni, S.Y., Chang, J., Chou, L., Zhai, W.Y., Comparison of osteoblast-like cell responses to calcium silicate and tricalcium phosphate ceramics in vitro (2007) J. Biomed. Mater. Res. B. Appl. Biomater, 80, pp. 174-183; Sarmento, C., Luklinska, Z.B., Brown, L., Anseau, M., De Aza, P.N., De Aza, S., In vitro behavior of osteoblastic cells cultured in the presence of pseudowollastonite ceramic (2004) J. Biomed. Mater. Res. A, 69 A, pp. 351-358
Keywords: Apatite; Apatites; article; Bioceramics; Biocompatibility; bone marrow cell; bone prosthesis; Bone Substitutes; Calcium Compounds; calcium derivative; calcium phosphate; calcium silicate; cell activity; cell adhesion; Cell culture; cell differentiation; cell enlargement; cell growth; cell proliferation; cell structure; cell viability; Cells, Cultured; ceramics; chemistry; confocal laser microscopy; crystal structure; Crystallization; cytology; glass; Glass ceramics; human; human cell; Humans; in vitro study; materials testing; Mesenchymal stem cell; Mesenchymal Stem Cells; methodology; osteoblast; Osteoblasts; physiology; priority journal; protein content; Scanning electron microscopy; silicate; Silicates; Surface Properties; surface property; Tissue regeneration; Wollastonite; X ray fluorescence

In vivo evaluation of highly macroporous ceramic scaffolds for bone tissue engineering - Teixeira, S.; Fernandes, H.; Leusink, A.; Van Blitterswijk, C.; Ferraz, M.P.; Monteiro, F.J.; De Boer, J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
During the last decades, different materials of both natural and synthetic origin have been developed with the aim of inducing and controlling osteogenic differentiation of mesenchymal stem cells (MSCs). In order for that to happen, it is necessary that the material to be implanted obey a series of requirements, namely: osteoconduction, biocompatibility, and biodegradability. Additionally, they must be low-priced, easy to produce, shape, and store. Hydroxyapatite (HA) is a well known ceramic with a composition similar to the mineral component of bone and is highly biocompatible and easy to obtain and/or process. On the other hand, collagen is the main structural protein present in the human body and bone. In this study, a polymer replication method was applied and a highly porous HA scaffold was produced. Collagen was later incorporated to improve the biological properties of the scaffold while resembling the bone composition. The scaffolds were characterized by means of scanning electron microscopy, Fourier transform infrared spectroscopy and energy dispersive spectroscopy. In vitro and in vivo testing was performed in all scaffolds produced. The goal of this study was to evaluate the in vivo osteogenic potential of MSCs from two different species seeded on the different HA based porous scaffolds with collagen type I. The results indicate that all scaffolds exhibit relevant bone formation, being more prominent in the case of the HA scaffolds. © 2009 Wiley Periodicals, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32532PubMed ID: 19591232Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomaterials, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: sandra_teixeira3@yahoo.comChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Biocompatible Materials; Ceramics; Durapatite, 1306-06-5References: Jones, A.C., Milthorpe, B., Averdunk, H., Limaye, A., Senden, T.J., Sakellariou, A., Sheppard, A.P., Dwdw, H., Analysis of 3D bone ingrowth into polymer scaffolds via micro-computed tomography imaging (2004) Biomaterials, 25, pp. 4947-4954;Aizawa, M., Shinoda, H., Uchida, H., Itatani, K., Okada, I., Matsumoto, M., Toyama, Y., Development and biological evaluation of apatite fibre scaffolds with large pore size and high porosity for bone regeneration (2003) Bioceramics, 240-242, pp. 647-650; Ebaretonbofa, E., Evans, J.R.G., High porosity hydroxyapatite foam scaffolds for bone substitute (2002) J Porous Mater, 9, pp. 257-263; Wissink, M.J.B., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Immobilization of heparin to EDC/NHS-crosslinked collagen (2001) Characterization and in Vitro Evaluation. Biomaterials, 22, pp. 151-163; Lee, C.H., Singla, A., Lee, Y., Biomedical applications of collagen (2001) Int J Pharm, 221, pp. 1-22; Jensen, T.B., Overgaard, S., Lind, M., Rahbek, O., Bünger, C., Søballe, K., Osteogenic protein 1 device increases bone formation and bone graft resorption around cementless implants (2002) Acta Orthop Scand, 73, pp. 31-39; Niemeyer, P., Krause, U., Fellenberg, J., Kasten, P., Seckinger, A., Ho, A.D., Simank, H.G., Evaluation of mineralized collagen and alpha-tricalcium phosphate as scaffolds for tissue engineering of bone using human mesenchymal stem cells (2004) Cells Tissues Organs, 177, pp. 68-78; Yang, X.B., Bhatnagar, R.S., Li, S., Oreffo, R.O., Biomimetic collagen scaffolds for human bone cell growth and differentiation (2004) Tissue Eng, 10, pp. 1148-1159; Xu, C., Wang, Y., Yu, X., Chen, X., Li, X., Yang, X., Li, S., Xiang, A.P., Evaluation of human mesenchymal stem cells response to biomimetic bioglass-collagen-hyaluronic acidphosphatidylserine composite scaffolds for bone tissue engineering (2009) J Biomed Mater Res A, 88, pp. 264-273; Kikuchi, M., Matsumoto, H.N., Yamada, T., Koyama, Y., Takakuda, K., Tanaka, J., Glutaraldehyde cross-linked hydroxyapatite/collagen self-organized nanocomposites (2004) Biomaterials, 25, pp. 63-69; Liao, S., Wang, W., Uo, M., Ohkawa, S., Akasaka, T., Tamura, K., Cui, F., Watari, F., A three-layered nano-carbonated hydroxyapatite/ collagen/PLGA composite membrane for guided tissue regeneration (2005) Biomaterials, 26, pp. 7564-7571; Liao, S., Watari, F., Zhu, Y., Uo, M., Akasaka, T., Wang, W., Xu, G., Cui, F., The degradation of the three layered nano-carbonated hydroxyapatite/ collagen/PLGA composite membrane in vitro (2007) Dent Mater, 23, pp. 1120-1128; Zhang, S.M., Cui, F.Z., Liao, S.S., Zhu, Y., Han, L., Synthesis and biocompatibility of porous nano-hydroxyapatite/collagen/ alginate composite (2003) J Mater Sci, 14, pp. 641-645; Glowacki, J., Mizuno, S., Collagen scaffolds for tissue engineering (2008) Biopolymers, 89, pp. 338-344; Hao, W., Hu, Y.Y., Wei, Y.Y., Pang, L., Lv, R., Bai, J.P., Xiong, Z., Jiang, M., Collagen I gel can facilitate homogenous bone formation of adipose-derived stem cells in PLGA-beta-TCP scaffold (2008) Cells Tissues Organs, 187, pp. 89-102; Liuyun, J., Yubao, L., Li, Z., Jianguo, L., Preparation and properties of a novel bone repair composite: Nano-hydroxyapatite/ chitosan/carboxymethyl cellulose (2008) J Mater Sci, 19, pp. 981-987; Zhou, G., Li, Y., Zhang, L., Zuo, Y., Jansen, J.A., Preparation and characterization of nano-hydroxyapatite/chitosan/konjac glucomannan composite (2007) J Biomed Mater Res, 83, pp. 931-939; Hua, Y., Ning, C., Xiaoying, L., Buzhong, Z., Wei, C., Xiaoling, S., Natural hydroxyapatite/chitosan composite for bone substitute materials (2005) Conf Proc IEEE Eng Med Biol Soc, 5, pp. 4888-4891; Oliveira, J.M., Rodrigues, M.T., Silva, S.S., Malafaya, P.B., Gomes, M.E., Viegas, C.A., Dias, I.R., Reis, R.L., Novel hydroxyapatite/ chitosan bilayered scaffold for osteochondral tissue- Engineering applications: Scaffold design and its performance when seeded with goat bone marrow stromal cells (2006) Biomaterials, 27, pp. 6123-6137; Kong, L., Gao, Y., Cao, W., Gong, Y., Zhao, N., Zhang, X., Preparation and characterization of nano-hydroxyapatite/chitosan composite scaffolds (2005) J Biomed Mater Res, 75, pp. 275-282; Zhao, F., Yin, Y., Lu, W.W., Leong, J.C., Zhang, W., Zhang, J., Zhang, M., Yao, K., Preparation and histological evaluation of biomimetic three-dimensional hydroxyapatite/chitosan-gelatin network composite scaffolds (2002) Biomaterials, 23, pp. 3227-3234; Everaerts, F., Torrianni, M., Hendriks, M., Feijen, J., Biomechanical properties of carbodiimide crosslinked collagen: Influence of the formation of ester crosslinks (2008) J Biomed Mater Res A, 85, pp. 547-555; Vrana, N.E., Builles, N., Kocak, H., Gulay, P., Justin, V., Malbouyres, M., Ruggiero, F., Hasirci, V., EDC/NHS cross-linked collagen foams as scaffolds for arti.cial corneal stroma (2007) J Biomater Sci, 18, pp. 1527-1545; Wissink, M.J.B., Beernink, R., Scharenborg, N.M., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Endothelial cell seeding of (heparinized) collagen matrices: Effects of bFGF pre-loading on proliferation (after low density seeding) and pro-coagulant factors (2000) J Control Release, 67, pp. 141-155; Wissink, M.J.B., Van Luyn, M.J.A., Beernink, R., Dijk, F., Poot, A.A., Engbers, G.H.M., Beugeling, T., Feijen, J., Endothelial cell seeding on crosslinked collagen: Effects of crosslinking on endothelial cell proliferation and functional parameters (2000) Thrombosis Haemostasis, 84, pp. 325-331; Teixeira, S., Ferraz, M.P., Monteiro, F.J., Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies (2008) J Mater Sci Mater Med, 19, pp. 855-859; Wissink, M.J.B., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Binding and release of basic fibroblast growth factor from heparinized collagen matrices (2001) Biomaterials, 22, pp. 2291-2299; Wissink, M.J.B., Beernink, R., Poot, A.A., Engbers, G.H.M., Beugeling, T., Van Aken, W.G., Feijen, J., Improved endothelialization of vascular grafts by local release of growth factor from heparinized collagen matrices (2000) J Control Release, 64, pp. 103-114; Habibovic, P., Yuan, H., Van Den Doel, M.A., Sees, T.M., Van Blitterswijk, C.A., De Groot, K., Relevance of osteoinductive biomaterials in critical-sized orthotopic defect (2006) J Orthop Res, 24, pp. 867-876; Habibovic, P., Sees, T.M., Van Den Doel, M.A., Van Blitterswijk, C.A., De Groot, K., Osteoinduction by biomaterials-physicochemical and structural influences (2006) J Biomed Mater Res A, 77, pp. 747-762; Both, S.K., Van Der Muijsenberg, A.J., Van Blitterswijk, C.A., De Boer, J., De Bruijn, J.D., A rapid and ef.cient method for expansion of human mesenchymal stem cells (2007) Tissue Eng, 13, pp. 3-9; Habibovic, P., Gbureck, U., Doillon, C.J., Bassett, D.C., Van Blitterswijk, C.A., Barralet, J.E., Osteoconduction and osteoinduction of low-temperature 3D printed bioceramic implants (2008) Biomaterials, 29, pp. 944-953; Teixeira, S., Oliveira, S., Ferraz, M.P., Monteiro, F.J., Three dimensional macroporous calcium phosphate scaffolds for bone tissue engineering (2008) Key Eng Mater, 361-363 (2), pp. 947-950; Teixeira, S., Rodriguez, M.A., Pena, P., De Aza, A.H., De Aza, S., Ferraz, M.P., Monteiro, F.J., Physical characterization of hydroxyapatite porous scaffolds for tissue engineering (2009) Mat Sci Eng: C, 29, pp. 1510-1514; Kim, H.W., Knowles, J.C., Kim, H.E., Hydroxyapatite porous scaffold engineered with biological polymer hybrid coating for antibiotic Vancomycin release (2005) J Mater Sci, 16, pp. 189-195; Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Siddappa, R., Fernandes, H., Liu, J., Van Blitterswijk, C., De Boer, J., The response of human mesenchymal stem cells to osteogenic signals and its impact on bone tissue engineering (2007) Curr Stem Cell Res Ther, 2, pp. 209-220; Olivo, C., Alblas, J., Verweij, V., Van Zonneveld, A.J., Dhert, W.J., Martens, A.C., In vivo bioluminescence imaging study to monitor ectopic bone formation by luciferase gene marked mesenchymal stem cells (2008) J Orthop Res, 26, pp. 901-909; Yuan, H., Van Blitterswijk, C.A., De Groot, K., De Bruijn, J.D., A comparison of bone formation in biphasic calcium phosphate (BCP) and hydroxyapatite (HA) implanted in muscle and bone of dogs at different time periods (2006) J Biomed Mater Res A, 78, pp. 139-147; Habibovic, P., Li, J., Van Der Valk, C.M., Meijer, G., Layrolle, P., Van Blitterswijk, C.A., Groot, K., Biological performance of uncoated and octacalcium phosphate-coated Ti6Al4V (2005) Biomaterials, 26, pp. 23-36; Habibovic, P., Yuan, H., Van Der Valk, C.M., Meijer, G., Van Blitterswijk, C.A., De Groot, K., 3D microenvironment as essential element for osteoinduction by biomaterials (2005) Biomaterials, 26, pp. 3565-3575
Keywords: animal cell; animal experiment; animal model; Animals; article; Biocompatibility; Biocompatible Materials; Biodegradation; Bone; Bone and Bones; Bone formation; bone tissue; Calcium; Calcium alloys; calcium phosphate; Calcium phosphates; Cell Count; Cell culture; Cell Culture Techniques; Cells, Cultured; cellular distribution; Ceramic materials; ceramics; Collagen; collagen type 1; Durapatite; Energy dispersive spectroscopy; Flowcharting; Fourier transform infrared spectroscopy; Humans; hydroxyapatite; Hydroxylation; in vitro study; In vivo bone formation; in vivo study; In-vivo; infrared spectroscopy; Macroporous; Macroporous scaffolds; male; materials testing; Mesenchymal stem cell; Mesenchymal Stem Cells; Mice; Microscopy, Electron, Scanning; nonhuman; ossification; Osteogenesis; porous polymer; rat; Rats; Rats, Wistar; Scaffolds; Scanning electron microscopy; Spectroscopy, Fourier Transform Infrared; Stem cells; Tissue engineering; tissue scaffold; Tissue Scaffolds

Influence of crystallite size of nanophased hydroxyapatite on fibronectin and osteonectin adsorption and on MC3T3-E1 osteoblast adhesion and morphology - Ribeiro, N.; Sousa, S.R.; Monteiro, F.J. (Journal of Colloid and Interface ScienceJ. Colloid Interface Sci., 2010)
The characteristic topographical features (crystallite dimensions, surface morphology and roughness) of bioceramics may influence the adsorption of proteins relevant to bone regeneration. This work aims at analyzing the influence of two distinct nanophased hydroxyapatite (HA) ceramics, HA725 and HA1000 on fibronectin (FN) and osteonectin (ON) adsorption and MC3T3-E1 osteoblast adhesion and morphology. Both substrates were obtained using the same hydroxyapatite nanocrystals aggregates and applying the sintering temperatures of 725°C and 1000°C, respectively. The two proteins used in this work, FN as an adhesive glycoprotein and ON as a counter-adhesive protein, are known to be involved in the early stages of osteogenesis (cell adhesion, mobility and proliferation). The properties of the nanoHA substrates had an important role in the adsorption behavior of the two studied proteins and clearly affected the MC3T3-E1 morphology, distribution and metabolic activity. HA1000 surfaces presenting slightly larger grain size, higher root-mean-square roughness (Rq), lower surface area and porosity, allowed for higher amounts of both proteins adsorbed. These substrates also revealed increased number of exposed FN cell-binding domains as well as higher affinity for osteonectin. Regarding the osteoblast adhesion results, improved viability and cell number were found for HA1000 surfaces as compared to HA725 ones, independently of the presence or type of adsorbed protein. Therefore the osteoblast adhesion and metabolic activity seemed to be more sensitive to surfaces morphology and roughness than to the type of adsorbed proteins. © 2010 Elsevier Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JCISAdoi: 10.1016/j.jcis.2010.08.013PubMed ID: 20810127Language of Original Document: EnglishCorrespondence Address: Ribeiro, N.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: nribeiro@ineb.up.ptChemicals/CAS: fibronectin, 86088-83-7; hydroxyapatite, 1306-06-5, 51198-94-8; osteonectin, 104052-78-0; protein, 67254-75-5; Ceramics; Durapatite, 1306-06-5; Fibronectins; OsteonectinReferences: Griffith, L.G., Naughton, G., (2002) Science, 295, p. 1009;Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., (2000) J. Biomed. Mater. Res., 51, pp. 475-483; Webster, T.J., Siegel, R.W., Bizios, R., (1999) Biomaterials, 20, pp. 1221-1227; Jun, I.K., Jang, J.H., Kim, H.W., Kim, H.E., (2005) J. Mater. Sci., 40, pp. 2891-2895; Geiger, B., Bershadsky, A., Pankov, R., Yamada, K.M., (2001) Nat. Rev. Mol. Cell Biol., 2, pp. 793-805; Globus, R.K., Doty, S.B., Lull, J.C., Holmuhamedov, E., Humphries, M.J., Damsky, C.H., (1998) J. Cell Sci., 111, pp. 1385-1393; Moursi, A.M., Damsky, C.H., Lull, J., Zimmerman, D., Doty, S.B., Aota, S.I., Globus, R.K., (1996) J. Cell Sci., 109, pp. 1369-1380; Garcia, A.J., Vega, M.D., Boettiger, D., (1999) Mol. Biol. Cell, 10, pp. 785-798; Petrie, T.A., Capadona, J.R., Reyes, C.D., Garcia, A.J., (2006) Biomaterials, 27, pp. 5459-5470; Dolatshahi-Pirouz, A., Jensen, T., Foss, M., Chevallier, J., Besenbacher, F., (2009) Langmuir, 25, pp. 2971-2978; Shen, J.-W., Wu, T., Wang, Q., Pan, H.-H., (2008) Biomaterials, 29, pp. 513-532; Brekken, R.A., Sage, E.H., (2000) Matrix Biol., 19, pp. 569-580; Termine, J.D., Kleinman, H.K., Whitson, S.W., Conn, K.M., McGarvey, M.L., Martin, G.R., (1981) Cell, 26, pp. 99-105; Liao, S., Ngiam, M., Chan, C.K., Ramakrishna, S., (2009) Biomed. Mater., 4; Sarvestani, A.S., He, X., Jabbari, E., (2008) Eur. Biophys. J. Biophys. Lett., 37, pp. 229-234; Majeska, R.J., Cell Biology of Bone (1934), pp. 2-3. , in: S.C. Cowin (Ed.), Bone Mechanics HandbookKoblinski, J.E., Wu, M., Demeler, B., Jacob, K., Kleinman, H.K., (2005) J. Cell Sci., 118, pp. 2965-2974; O'Brien, J., Wilson, I., Orton, T., Pognan, F., (2000) Eur. J. Biochem., 267, pp. 5421-5426; Ribeiro, C.C., Gibson, I., Barbosa, M.A., (2006) Biomaterials, 27, pp. 1749-1761; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., (1999) J. Biomed. Mater. Res., 45, pp. 370-375; Suzuki, T., Nishizawa, K., Yokogawa, Y., Nagata, F., Kawamoto, Y., Kameyama, T., (1996) J. Ferment. Bioeng., 81, pp. 226-232; Suzuki, T., Yamamoto, T., Toriyama, M., Nishizawa, K., Yokogawa, Y., Mucalo, M.R., Kawamoto, Y., Kameyama, T., (1997) J. Biomed. Mater. Res., 34, pp. 507-517; Holland, N.B., Marchant, R.E., (2000) J. Biomed. Mater. Res., 51, pp. 307-315; Kothapalli, C., Wei, M., Vasiliev, A., Shaw, M.T., (2004) Acta Mater., 52, pp. 5655-5663; Sousa, S.R., Manuela Bras, M., Moradas-Ferreira, P., Barbosa, M.A., (2007) Langmuir, 23, pp. 7046-7054; Rouahi, M., Champion, E., Gallet, O., Jada, A., Anselme, K., (2006) Colloids Surf., B - Biointerfaces, 47, pp. 10-19; dos Santos, E.A., Farina, M., Soares, G.A., Anselme, K., (2008) J. Mater. Sci. - Mater. Med., 19, pp. 2307-2316; Amaral, I.F., Unger, R.E., Fuchs, S., Mendonca, A.M., Sousa, S.R., Barbosa, M.A., Pego, A.P., Kirkpatrick, C.J., (2009) Biomaterials, 30, pp. 5465-5475; Sousa, S.R., Moradas-Ferreira, P., Barbosa, M.A., (2005), pp. 1173-1178. , TiO2 type influences fibronectin adsorption, in: 19th Conference of the European-Society-for-Biomaterials, Springer, Sorrento, ItalyGoldstein, A.S., DiMilla, P.A., (2002) J. Biomed. Mater. Res., 59, pp. 665-675; Michael, K.E., Vernekar, V.N., Keselowsky, B.G., Meredith, J.C., Latour, R.A., Garcia, A.J., (2003) Langmuir, 19, pp. 8033-8040; Anselme, K., Bigerelle, M., (2005) Acta Biomater., 1, pp. 211-222; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res., 49, pp. 155-166; Wang, C., Duan, Y., Markovic, B., Barbara, J., Rolfe Howlett, C., Zhang, X., Zreiqat, H., (2004) Biomaterials, 25, pp. 2949-2956; Smith, I.O., McCabe, L.R., Baumann, M.J., (2006) Int. J. Nanomed., 1, pp. 189-194; Bernards, M.T., Qin, C.L., Jiang, S.Y., Bone osteopontin, and bovine serum albumin (2008) Colloids Surf., B - Biointerfaces, 64, pp. 236-247; Durrieu, M.C., Pallu, S., Guillemot, F., Bareille, R., Amedee, J., Baquey, C., Labrugere, C., Dard, M., (2004) J. Mater. Sci. - Mater. Med., 15, pp. 779-786; Itoh, D., Yoneda, S., Kuroda, S., Kondo, H., Umezawa, A., Ohya, K., Ohyama, T., Kasugai, S., (2002) J. Biomed. Mater. Res., 62, pp. 292-298; Funk, S.E., Sage, E.H., (1993) J. Cell. Physiol., 154, pp. 53-63; Hagan, S., Hiscott, P., Sheridan, C., Wong, D., Grierson, I., McGalliard, J., (2003) Mol. Vis., 9, pp. 87-92; Deligianni, D., Korovessis, P., Porte-Derrieu, M.C., Amedee, J., (2005) J. Spinal Disord. Technol., 18, pp. 257-262; Nelson, M., Balasundaram, G., Webster, T.J., (2006) Int. J. Nanomed., 1, pp. 339-349
Keywords: Adhesion; Adhesive proteins; Adsorption; Adsorption behavior; Animals; Apatite; article; Bioceramics; Biological materials; Biomaterials; bone development; Bone Regeneration; cell adhesion; Cell Count; cell metabolism; cell motility; Cell number; cell proliferation; cell strain 3T3; cell structure; Cell-binding domain; Cells, Cultured; cellular distribution; ceramics; controlled study; Crystallite dimension; Crystallite size; Crystallization; Durapatite; Fibronectin; Fibronectin adsorption; Fibronectins; glycoprotein; grain; Grain size; human; human cell; hydroxyapatite; Hydroxyapatite nanocrystals; MC3T3-E1; Metabolic activity; metabolism; Mice; morphology; Nano-HA; nanocrystal; nanoparticles; Nanophased hydroxyapatite; osteoblast; Osteoblast adhesion; Osteoblast morphology; Osteoblasts; Osteogenesis; osteonectin; Osteonectin adsorption; Particle Size; porosity; priority journal; protein; Proteins; Root mean square roughness; Sintering; Sintering temperatures; Surface area; Surface Properties; surface property; Surface roughness; temperature; Topographical features

Innovative macroporous granules of nanostructured-hydroxyapatite agglomerates: Bioactivity and osteoblast-like cell behaviour - Laranjeira, M.S.; Fernandes, M.H.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
To modulate the biological response of implantable granules, two types of bioactive porous granules composed of nanostructured-hydroxyapatite (HA) agglomerates and microstructured-HA, respectively, were prepared using a polyurethane sponge impregnation and burnout method. The resulting granules presented a highly porous structure with interconnected porosity. Both types of granules were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and mercury intrusion porosimetry. Results showed that nanostructed-HA granules presented higher surface area and porosity than microstructured-HA granules. In vitro testing using MG63 human osteoblast-like cells showed that on both types of surfaces cells were able to adhere, proliferate, and migrate through the macropores, and a higher growth rate was achieved on nanostructured-HA granules than on microstructured-HA granules (76 and 40%, respectively). In addition, these cells maintained similar expression levels of osteoblastic-associated markers namely collagen type I, alkaline phosphatase, bone morphogenetic protein-2, macrophage colony-stimulating factor, and osteoprotegerin. These innovative nanostructured-HA granules may be considered as promising bioceramic alternative matrixes for bone regeneration and drug release application. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32916PubMed ID: 20845490Language of Original Document: EnglishCorrespondence Address: Laranjeira, M. S.; Divisão de Biomateriais, INEB-Instituto de Engenharia Biomédica, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: dce06004@fe.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; colony stimulating factor 1, 81627-83-0; hydroxyapatite, 1306-06-5, 51198-94-8; osteoprotegerin, 205944-50-9; polyurethan, 61789-63-7; Biocompatible Materials; Biological Markers; Durapatite, 1306-06-5; PolyurethanesReferences: Ferraz, M., Monteiro, F., Manuel, C., Hydroxyapatite nanoparticles: A review of preparation methodologies (2004) J Appl Biomater Biomech, 2, pp. 74-80;Murugan, R., Ramakrishna, S., Development of nanocomposites for bone grafting (2005) Compos Sci Technol, 65, pp. 2385-2406; Wahl, D., Czernuszka, J.T., Collagen-hydroxyapatite composites for hard tissue repair (2006) Eur Cell Mater, 11, pp. 43-46; Chen, Q.Z., Wong, C.T., Lu, W.W., Cheung, K.M., Leong, J.C., Luk, K.D., Strengthening mechanisms of bone bonding to crystalline hydroxyapatite in vivo (2004) Biomaterials, 25, pp. 4243-4254; Watari, F., Yokoyama, A., Gelinsky, M., Pompe, W., Conversion of functions by nanosizing from osteoconductivity to bone substitutional properties in apatite (2007) Interface Oral Health Sci, 23, pp. 139-148; Nihouannen, D., Duval, L., Lecomte, A., Julien, M., Guicheux, J., Daculsi, G., Layrolle, P., Interactions of total bone marrow cells with increasing quantities of macroporous calcium phosphate ceramic granules (2007) J Mater Sci Mater Med, 18, pp. 1983-1990; Le Nihouannen, D., Daculsi, G., Saffarzadeh, A., Gauthier, O., Delplace, S., Pilet, P., Layrolle, P., Ectopic bone formation by microporous calcium phosphate ceramic particles in sheep muscles (2005) Bone, 36, pp. 1086-1093; Kalita, S.J., Bhardwaj, A., Bhatt, H.A., Nanocrystalline calcium phosphate ceramics in biomedical engineering (2007) Mater Sci Eng C, 27, pp. 441-449; Kong, L.B., Ma, J., Boey, F., Nanosized hydroxyapatite powders derived from coprecipitation process (2002) J Mater Sci, 37, pp. 1131-1134; Habibovic, P., Kruyt, M.C., Juhl, M.V., Clyens, S., Martinetti, R., Dolcini, L., Theilgaard, N., Blitterswijk, C., Comparative in vivo study of six hydroxyapatite-based bone graft substitutes (2008) J Orthop Res, 26, pp. 1363-1370; Simon, J.L., Michna, S., Lewis, J.A., Rekow, E.D., Thompson, V.P., Smay, J.E., Yampolsky, A., Ricci, J.L., In vivo bone response to 3D periodic hydroxyapatite scaffolds assembled by direct ink writing (2007) J Biomed Mater Res A, 83, pp. 747-758; Clarke, S.A., Hoskins, N.L., Jordan, G.R., Henderson, S.A., Marsh, D.R., In vitro testing of advanced JAX TM bone void filler system: Species differences in the response of bone marrow stromal cells to b tri-calcium phosphate and carboxymethylcellulose gel (2007) J Mater Sci Mater Med, 18, pp. 2283-2290; Wei, G., Ma, P.X., Structure and properties of nano-hydroxyapatite/polymer composite scaffolds for bone tissue engineering (2004) Biomaterials, 25, pp. 4749-4757; Xu, T., Zhang, N., Nichols, H.L., Shi, D., Wen, X., Modification of nanostructured materials for biomedical applications (2007) Mater Sci Eng C, 27, pp. 579-594; Mateus, A.Y.P., Ferraz, M.P., Monteiro, F.J., Microspheres based on hydroxyapatite nanoparticles aggregates for bone regeneration (2007) Key Eng Mater, 330-332, pp. 243-246; Potoczek, M., Zima, A., Paszkiewicz, Z., Slosarczyk, A., Manufacturing of highly porous calcium phosphate bioceramics via gel-casting using agarose (2009) Ceram Int, 35, pp. 2249-2254; Okamoto, M., Dohi, Y., Ohgushi, H., Shimaoka, H., Ikeuchi, M., Matsushima, A., Yonemasu, K., Hosoi, H., Influence of the porosity of hydroxyapatite ceramics on in vitro and in vivo bone formation by cultured rat bone marrow stromal cells (2006) J Mater Sci Mater Med, 17, pp. 327-336; Tas, A.C., Preparation of porous apatite granules from calcium phosphate cement (2008) J Mater Sci Mater Med, 19, pp. 2231-2239; Joschek, S., Nies, B., Krotz, R., Gokpferich, A., Chemical and physicochemical characterization of porous hydroxyapatite ceramics made of natural bone (2000) Biomaterials, 21, pp. 1645-1658; Turhani, D., Cvikl, B., Watzinger, E., Weißenböck, M., Yerit, K., Thurnher, D., Lauer, G., Ewers, R., In vitro growth and differentiation of osteoblast-like cells on hydroxyapatite ceramic granule calcified from red algae (2005) J Oral Maxillofac Surg, 63, pp. 793-799; Teixeira, S., Ferraz, M.P., Monteiro, F.J., Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies (2008) J Mater Sci Mater Med, 19, pp. 855-859; Kim, Z., Oak, J., Kimura, H., Goto, T., Inoue, A., Yoon, S., Architecture of porous hydroxyapatite scaffolds using polymer foam process (2009) J Biomech Sci Eng, 4, pp. 377-383; Chevalier, E., Viana, M., Cazalbou, S., Makein, L., Dubois, J., Chulia, D., Ibuprofen-loaded calcium phosphate granules: Combination of innovative characterization methods to relate mechanical strength to drug location (2010) Acta Biomater, 6, pp. 266-274; Taboas, J.M., Maddox, R.D., Krebsbach, P.H., Hollister, S.J., Indirect solid free form fabrication of local and global porous, biomimetic and composite 3D polymer-ceramic scaffolds (2003) Biomaterials, 24, pp. 181-194; Wang, X., Ruan, J., Chen, Q., Effects of surfactants on the microstructure of porous ceramic scaffolds fabricated by foaming for bone tissue engineering (2009) Mater Res Bull, 44, pp. 1275-1279; Mateus, A.Y.P., Barrias, C.C., Ribeiro, C., Ferraz, M.P., Monteiro, F.J., Comparative study of nanohydroxyapatite microspheres for medical applications (2008) J Biomed Mater Res A, 86, pp. 483-493; Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Panda, R.N., Hsieh, M.F., Chung, R.J., Chin, T.S., FTIR, XRD, SEM and solid state NMR investigations of carbonate-containing hydroxyapatite nano-particles synthesized by hydroxide-gel technique (2003) J Phys Chem Solids, 64, pp. 193-199; Penel, G., Leroy, G., Rey, C., Sombret, B., Huvenne, J.P., Bres, E., Infrared and Raman microspectrometry study of fluor-fluor-hydroxy and hydroxy-apatite powders (1997) J Mater Sci Mater Med, 8, pp. 271-276; Elliott, J.C., Holcomb, D.W., Young, R.A., Infrared determination of the degree of substitution of hydroxyl by carbonate ions in human dental enamel (1985) Calcif Tissue Int, 37, pp. 372-375; Rouahi, M., Gallet, O., Champion, E., Dentzer, J., Hardouin, P., Anselme, K., Influence of hydroxyapatite microstructure on human bone cell response (2006) J Biomed Mater Res A, 78, pp. 222-235; Fierz, F.C., Beckmann, F., Huser, M., Irsen, S.H., Leukers, B., Witte, F., Degistirici, O., Muller, B., The morphology of anisotropic 3D-printed hydroxyapatite scaffolds (2008) Biomaterials, 29, pp. 3799-3806; Singh, R., Lee, P.D., Lindley, T.C., Dashwood, R.J., Ferrie, E., Imwinkelried, T., Characterization of the structure and permeability of titanium foams for spinal fusion devices (2009) Acta Biomater, 5, pp. 477-487; Wei, J., Jia, J., Wu, F., Wei, S., Zhou, H., Zhang, H., Shin, J.W., Liu, C., Hierarchically microporous/macroporous scaffold of magnesium-calcium phosphate for bone tissue regeneration (2010) Biomaterials, 31, pp. 1260-1269; Rucker, M., Laschke, M.W., Junker, D., Carvalho, C., Tavassol, F., Mulhaupt, R., Gellrich, N.C., Menger, M.D., Vascularization and biocompatibility of scaffolds consisting of different calcium phosphate compounds (2007) J Biomed Mater Res A, 68, pp. 1002-1011; Klenke, F.M., Liu, Y., Yuan, H., Hunziker, E.B., Siebenrock, K.A., Hofstetter, W., Impact of pore size on the vascularization and osseointegration of ceramic bone substitutes in vivo (2007) J Biomed Mater Res A, 85, pp. 777-786; Lee, S.J., Choi, J.S., Park, K.S., Khang, G., Lee, Y.M., Lee, H.B., Response of MG63 osteoblast-like cells onto polycarbonate membrane surfaces with different micropore sizes (2004) Biomaterials, 25, pp. 4699-4707; Kim, H., Lee, E., Kim, H., Salih, V., Knowles, J.C., Effect of fluoridation of hydroxyapatite in hydroxyapatite- polycaprolactone composites on osteoblast activity (2005) Biomaterials, 25, pp. 4395-4404; Son, E., Do, H., Joo, H., Pyo, S., Induction of alkaline phosphatase activity by L-ascorbic acid in human osteoblastic cells: A potential role for CK2 and Ikaros (2007) Nutrition, 23, pp. 745-753; Guo, X., Gough, J.E., Xiao, P., Liu, J., Shen, Z., Fabrication of nanostructured hydroxyapatite and analysis of human osteoblastic cellular response (2007) J Biomed Mater Res A, 82, pp. 1022-1032; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Mendonça, G., Mendonça, D.B., Simões, L.G., Araújo, A.L., Leite, E.R., Duarte, W.R., Aragão, F.J., Cooper, L.F., The effects of implant surface nanoscale features on osteoblast-specific gene expression (2009) Biomaterials, 30, pp. 4053-4062
Keywords: Agglomeration; alkaline phosphatase; Apatite; article; Bioceramics; Biocompatible Materials; Biological Markers; Biological materials; Biological response; Biomaterials; Bone; bone morphogenetic protein 2; Bone morphogenetic protein-2; Bone Regeneration; cell adhesion; cell function; cell granule; cell migration; cell proliferation; Cells, Cultured; collagen type 1; Collagen type I; colony stimulating factor 1; Colony-stimulating factor; drug activity; Drug release; Durapatite; Expression levels; Fourier transform infrared spectroscopy; Fourier transforms; Granulation; Granules; growth rate; human; human cell; Human osteoblast-like cells; Humans; hydroxyapatite; In-vitro; infrared spectroscopy; Interconnected porosity; Macro-porosity; Macropores; Macroporosity; Macroporous; materials testing; matrix; Mercury (metal); Mercury intrusion porosimetry; Microscopy, Electron, Scanning; Microstructured; Nano-materials; Nano-structured; nanomaterial; Nanomaterials; Nanostructured materials; Nanostructures; osteoblast; Osteoblast response; Osteoblast-like cells; Osteoblasts; Osteoprotegerin; Phosphatases; polyurethan; Polyurethane sponge; Polyurethanes; porosity; Porous structures; Reverse Transcriptase Polymerase Chain Reaction; Scanning electron microscopy; SEM; Spectroscopy, Fourier Transform Infrared; Surface area; surface property; X ray diffraction; X-Ray Diffraction

An intrauterine pressure generator for educational simulation of labour and delivery - Bastos, L.F.; Lobo, M.F.; van Meurs, W.L.; Ayres-de-Campos, D. (Medical Engineering and PhysicsMed. Eng. Phys., 2010)
Simulation provides a risk free and controllable environment for training of healthcare providers. The limited realism of available simulators and training programs impedes immersive training in obstetric emergencies. In developed countries, intrapartum monitoring in high-risk cases involves continuous evaluation of foetal heart rate and uterine contractions signals. We present an essential component of a high-fidelity simulator for normal and critical situations in labour and delivery, namely an intrauterine pressure generator. The signal model behind the generator consists of a truncated Gaussian curve with the programmable features: amplitude, frequency, duration, and resting tone. Through analysis of 44. h of physiological data, we demonstrate that the natural variability of these features and of the baseline pressure can be approximated by deterministic trends and stationary stochastic processes. Signal parameters can be controlled by simulation instructors, scripts, or other models to reflect different patients, pathologies, and evolving clinical situations. Twelve 40-min tracings reflecting three different patients in labour were presented to three clinical experts, who attributed similar realism scores to simulated and to real tracings. © 2010 IPEM.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: MEPHEdoi: 10.1016/j.medengphy.2010.04.015PubMed ID: 20494606Language of Original Document: EnglishCorrespondence Address: Bastos, L.F.; Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Rua Dr. Roberto Frias, s/n, I302, 4200-465 Porto, Portugal; email: lbastos@fe.up.ptReferences: Carlin, A., Alfirevic, Z., Intrapartum foetal emergencies (2006) Semin Foetal Neonatal Med, 11, pp. 150-157;Draycott, T., Sibanda, T., Owen, L., Akande, V., Winter, C., Reading, S., Does training in obstetric emergencies improve neonatal outcome? (2006) BJOG, 113, pp. 177-182; Daniels, K., Lipman, S., Harney, K., Arafeh, J., Druzin, M., Use of simulation based team training for obstetric crises in resident education (2008) Simul Healthc, 3, pp. 154-160; Gardner, R., Walzer, T.B., Simon, R., Raemer, D.B., Obstetric simulation as a risk control strategy: course design and evaluation (2008) Simul Healthc, 3, pp. 119-127; Pliego, J.F., Wehbe-Janek, H., Rajab, M.H., Browning, J.L., Fothergill, R.E., Ob/Gyn boot camp using high-fidelity human simulators: enhancing residents' perceived competency, confidence in taking a leadership role, and stress hardiness (2008) Simul Healthc, 3, pp. 82-89; Crofts, J.F., Bartlett, C., Ellis, D., Hunt, L.P., Fox, R., Draycott, T.J., Training for shoulder dystocia: a trial of simulation using low-fidelity and high-fidelity mannequins (2006) Obstet Gynecol (New York, 1953), 108, pp. 1477-1485; Gardner, R., Raemer, D.B., Simulation in obstetrics and gynecology (2008) Obstet Gynecol Clin North Am, 35, pp. 97-127; (2001) The use of electronic foetal monitoring: the use and interpretation of cardiotocography in intrapartum foetal surveillance, , Royal-College-of-Obstetricians-and-Gynaecologists, RCOG, London; (2006) Intrapartum foetal surveillance: clinical guidelines, , Royal-Australian-and-New-Zealand-College-of-Obstetricians-and-Gynaecologists, RANZCOG, Melbourne; Bracero, L.A., Roshanfekr, D., Byrne, D.W., Analysis of antepartum foetal heart rate tracing by physician and computer (2000) J Matern Foetal Med, 9, pp. 181-185; Doyle, C., Angelotti, T., Diagnosis of an unsuspected maternal hemorrhage via foetal heart rate tracing (2004) J Clin Anesth, 16, pp. 465-468; Donn, S.M., Sinha, S.K., Chiswick, M.L., (2002) Birth asphyxia and the brain: basic science and clinical implications, , Blackwell Publishing; Laros, J.R.K., Presidential address: medical-legal issues in obstetrics and gynecology (2005) Am J Obstet Gynecol, 192, pp. 1883-1889; Cusick, W., Smulian, J.C., Vintzileos, A.M., Intrapartum use of foetal heart rate monitoring, contraction monitoring, and amnioinfusion (1995) Clin Perinatol, 22, pp. 875-906; Vanner, T., Gardosi, J., Intrapartum assessment of uterine activity (1996) Baillieres Clin Obstet Gynaecol, 10, pp. 243-257; Bakker, P.C.A.M., Van Rijswijk, S., Van Rijsiwijk, S., van Geijn, H.P., Uterine activity monitoring during labor (2007) J Perinat Med, 35, pp. 468-477; Bakker, P.C.A.M., van Geijn, H.P., Uterine activity: implications for the condition of the foetus (2008) J Perinat Med, 36, pp. 30-37; Andersen, H.F., Barclay, M.L., A computer-model of uterine contractions based on discrete contractile elements (1995) Obstet Gynecol, 86, pp. 108-111. , J; Young, R.C., A computer model of uterine contractions based on action potential propagation and intercellular calcium waves (1997) Obstet Gynecol, 89, pp. 604-608. , A; Wray, S., Uterine contraction and physiological mechanisms of modulation (1993) Am J Physiol, 264, pp. C1-C18. , J; Wray, S., Kupittayanant, S., Shmygol, A., Smith, R.D., Burdyga, T., The physiological basis of uterine contractility: a short review (2001) Exp Physiol, 86, pp. 239-246; Vauge, C., Carbonne, B., Papiernik, E., Ferre, F., A mathematical model of uterine dynamics and its application to human parturition (2000) Acta Biotheor, 48, pp. 95-105. , J; Moreau, R., Pham, M.T., Redarce, T., Dupuis, O., Simulation of forceps extraction on a childbirth simulator (2008) Proceedings of the IEEE International Conference on Robotics and Automation (ICRA), pp. 1100-1105; Klavan, M., Laver, A.T., Boscola, M.A., (1977) Clinical concepts of foetal heart rate monitoring, , Hewlett-Packard Waltham, Mass; Parer, J.T., (1997) Handbook of foetal heart rate monitoring, , W.B. Saunders Company, Philadelphia; Maul, H., Maner, W.L., Olson, G., Saade, G.R., Garfield, R.E., Non-invasive transabdominal uterine electromyography correlates with the strength of intrauterine pressure and is predictive of labor and delivery (2004) J Matern Foetal Neonatal Med, 15, pp. 297-301; Cobo, E., Quintero, C.A., Strada, G., Zambrana, M.A., Uterine behavior in abruptio placentae. I. Contraction patterns and their reactivity to oxytocin (1965) Am J Obstet Gynecol, 93, pp. 1151-1156; Seitchik, J., Quantitating uterine contractility in clinical context (1981) Obstet Gynecol, 57, pp. 453-457; Burchell, H.J., Odendaal, H.J., de Wet, J.I., Badenhorst, P.N., Uterine contraction patterns in abruptio placentae (1985) S Afr Med J, 67, pp. 48-50; Harbert, G.M., Assessment of uterine contractility and activity (1992) Clin Obstet Gynecol, 35, pp. 546-558; Bruce, E.N., (2001) Biomedical signal processing and signal modeling, , Wiley-Interscience; Levinson, N., The Wiener RMS (root mean square) error criterion in filter design and prediction (1947) J Math Phys, 25, pp. 261-278; Paul, M.J., Smeltzer, J.S., Relationship of measured external tocodynamometry with measured internal uterine activity (1991) Am J Perinatol, 8, pp. 417-420; Miles, A.M., Monga, M., Richeson, K.S., Correlation of external and internal monitoring of uterine activity in a cohort of term patients (2001) Am J Perinatol, 18, pp. 137-140; van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit Comput, 13, pp. 317-324; van Meurs, W.L., Nikkelen, E., Good, M.L., Pharmacokinetic-pharmacodynamic model for educational simulations (1998) IEEE Trans Biomed Eng, 45, pp. 582-590
Keywords: article; Clinical situations; Computer simulation; delivery; Delivery, Obstetric; Developed countries; Educational simulations; Essential component; Female; Fetal monitoring; Gaussian curves; generator; Health care providers; Heart Rate, Fetal; Heart rates; High-fidelity simulators; Humans; Immersive; intrauterine pressure; labor; Labor, Obstetric; Labour and delivery; medical education; Medical educational simulation; muscle tone; Natural variability; normal distribution; Obstetrics; Physiological data; Pregnancy; Prenatal Diagnosis; Pressure; Pressure generators; priority journal; Random processes; Risk free; Signal generator; Signal generators; Signal models; Signal parameters; Signal Processing, Computer-Assisted; simulation; Stationary stochastic process; statistical model; statistical parameters; statistics; Stochastic Processes; Time Factors; Training program; Uterine activities; Uterine activity; Uterine Contraction; Uterine Monitoring; uterus contraction

Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics): Preface - Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2010)
Conference code: 81097Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Campilho, A.; University of Porto, Faculty of Engineering, Institute of Biomedical Engineering, 4200-465 Porto, Portugal; email: campilho@fe.up.pt

The MEE principle in data classification: A perceptron-based analysis - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Neural ComputationNeural Comp., 2010)
This letter focuses on the issue of whether risk functionals derived from information-theoretic principles, such as Shannon or Rényi's entropies, are able to cope with the data classification problem in both the sense of attaining the risk functional minimum and implying the minimum probability of error allowed by the family of functions implemented by the classifier, here denoted by min Pe. The analysis of this so-called minimization of error entropy (MEE) principle is carried out in a single perceptron with continuous activation functions, yielding continuous error distributions. In spite of the fact that the analysis is restricted to single perceptrons, it reveals a large spectrum of behaviors that MEE can be expected to exhibit in both theory and practice. In what concerns the theoretical MEE, our study clarifies the role of the parameters controlling the perceptron activation function (of the squashing type) in often reaching the minimum probability of error. Our study also clarifies the role of the kernel density estimator of the error density in achieving the minimum probability of error in practice. © 2010 Massachusetts Institute of Technology.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1162/NECO_a_00013PubMed ID: 20569178Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Porto 4200-465, Portugal; email: lmsilva@fe.up.ptReferences: Alexandre, L.A., Marques de Sá, J., Error entropy minimization for LSTM training (2006) Proceedings of the 16th International Conference on Artificial Neural Networks, pp. 244-253. , Berlin: Springer;Asuncion, A., Newman, D., (2007) UCI machine learning repository. Irvine University of California, Irvine, , http://www.ics.uci.edu/~mlearn/MLRepository.html, School of Information and Computer Sciences. Available online at; Bishop, C., (1995) Neural networks for pattern recognition, , New York: OxfordUniversity Press; Erdogmus, D., Hild K., II., Príncipe, J.C., Blind source separation using Rényi's α-marginal entropies (2002) Neurocomputing, 49, pp. 25-38; Erdogmus, D., Príncipe, J.C., Comparison of entropy and mean square error criteria in adaptive system training using higher order statistics (2000) Proceedings of the Intl. Conf. on ICA and Signal Separation, pp. 75-80. , Berlin: Springer-Verlag; Erdogmus, D., Príncipe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Erdogmus, D., Príncipe, J.C., Convergence properties and data efficiency of the minimum error entropy criterion in adaline training (2003) IEEE Transactions on Signal Processing, 51 (7), pp. 1966-1978; Gokcay, E., Príncipe, J.C., Information theoretic clustering (2002) IEEE Trans. on Pattern Analysis and Machine Learning, 24 (2), pp. 158-171; Han, L., Kernel partial least squares (K-PLS) for scientific data mining. Unpublished doctoral dissertation (2007) Rensselaer Polytechnic Institute; Hild, I.I., Erdogmus, K., Príncipe D., J.C., Blind source separation using Rényi's mutual information (2001) IEEE Signal Processing Letters, 8, pp. 174-176; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Jenssen, R., Hild, K., Erdogmus, D., Príncipe, J.-C., Eltoft, T., Clustering using Rényis entropy (2003) Proceedings of the Int. Joint Conference on Neural Networks, pp. 523-528. , Piscataway, NJ: IEEE Press; Johnson, N., Kotz, S., (1970) Continuous univariate distributions, , Hoboken, NJ:Wiley; Kapur, J., Maximum-entropy models in science and engineering (1993), (rev. ed.). Hoboken, NJ: WileyLagarias, J., Reeds, J.A., Wright, M.H., Wright, P.E., Convergence properties of the nelder-mead simplex method in low dimensions (1998) SIAM Journal of Optimization, 9 (1), pp. 112-147; Linsker, R., Self-organization in a perceptual network (1988) IEEE Computer, 21, pp. 105-117; Liu, W., Pokharel, P., Príncipe, J., Correntropy: Properties and applications in non-gaussian signal processing (2007) IEEE Transactions on Signal Processing, 55 (11), pp. 5286-5298; Parzen, E., On the estimation of a probability density function and the mode (1962) Annals of Mathematical Statistics, 33, pp. 1065-1076; Príncipe, J.C., Xu, D., Fisher, J., Information theoretic learning (2000) Unsupervised adaptive filtering, 1, pp. 265-319. , S. Haykin (Ed.), Blind source separation, Hoboken, NJ: Wiley; Rényi, A., (1970) Probability theory, , Dordrecht: North-Holland; Richard, M., Lippmann, R., Neural network classifiers estimate Bayesian a posteriori probabilities (1991) Neural Computation, 3, pp. 461-483; Santos, J., (2007) Data classification with neural networks and entropic criteria, , Unpublished doctoral dissertation, University of Porto; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Batch-sequential algorithm for neural networks trained with entropic criteria (2005) Proceedings of the International Conference on Artificial Neural Networks, pp. 91-96. , Berlin: Springer-Verlag; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Legclust-a clustering algorithm based on layered entropic subgraphs (2007) IEEE Transactions on Pattern Analysis and Machine Intelligence, 30 (1), pp. 62-75; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Sereno, F., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent engineering systems through artificial neural networks, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, & O. Ersoy (Eds.), Washington, DC: ASME; Silva, L.M., (2008) Neural networks with error-density risk functionals for data classification, , Unpublished doctoral dissertation, University of Porto; Silva, L.M., Embrechts, M., Santos, J.M., Marques de Sá, J., The influence of the risk functional in data classification with MLPs (2008) Proceedings of the International Conference on Artificial Neural Networks, pp. 185-194. , Berlin: Springer-Verlag; Silva, L.M., Felgueiras, C., Alexandre, L.A., Marques de Sá, J., Error entropy in classification problems: A univariate data analysis (2006) Neural Computation, 18 (9), pp. 2036-2061; Silva, L.M., Marques de Sá, J., Alexandre, L.A., Neural network classification using Shannon's entropy (2005) Proceedings of the European Symposium on Artificial Neural Networks, pp. 217-222. , Bruges: d-side; Stoller, D., Univariate two-population distribution free discrimination (1954) Journal of the American Statistical Association, 49, pp. 770-777; Thompson, J., Tapia, R., (1978) Nonparametric probability density estimation, , Baltimore, MD: Johns Hopkins University Press; Watanabe, S., Pattern recognition as a quest for minimum entropy (1981) Pattern Recognition, 13 (5), pp. 381-387
Keywords: algorithm; Algorithms; artificial intelligence; artificial neural network; automated pattern recognition; Computer simulation; entropy; letter; Mathematical Concepts; mathematical phenomena; Models, Statistical; Neural Networks (Computer); Pattern Recognition, Automated; standard; statistical model

A model for educational simulation of hemodynamic transitions at birth - Sá-Couto, C.D.; Andriessen, P.; van Meurs, W.L.; Ayres-de-Campos, D.; Sá-Couto, P.M. (Pediatric ResearchPediatr. Res., 2010)
Birth is characterized by swift and complex transitions in hemodynamic and respiratory variables. Unrecognized pathologies or incidents may quickly become fatal or cause permanent damage. This article introduces an essential component of an acute perinatal care simulator, namely a model for educational simulation of normal hemodynamic transitions seen during and shortly after birth. We explicitly formulate educational objectives and adapt a preexisting model for the simulation of neonatal cardiovascular physiology to include essential aspects of fetal hemodynamics. From the scientific literature, we obtain model parameters that characterize these aspects quantitatively. The fetal model is controlled by a time-and event-based script of changes occurring at birth, such as onset of breathing and cord clamping, and the transitory phase up to 24 h after birth. Comparison of simulation results with published target data confirms that realistic simulated hemodynamic vital signs are achieved. Copyright © 2010 International Pediatric Research Foundation, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: PEREBdoi: 10.1203/PDR.0b013e3181c2def3Language of Original Document: EnglishCorrespondence Address: Van Meurs, W. L.; INEB-Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: wvanmeurs@ineb.up.ptReferences: Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324;Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-9; Zijlmans, M., Sá-Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology (2009) Simul Healthc, 4, pp. 49-53; Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Ménigault, E., Vieyres, P., Lepoivre, B., Durand, A., Pourcelot, L., Berson, M., Fetal heart modelling based on a pressure-volume relationship (1997) Med Biol Eng Comput, 35, pp. 715-721; Pennati, G., Bellotti, M., Fumero, R., Mathematical modeling of the human foetal cardiovascular system based on Doppler ultrasound data (1997) Med Eng Phys, 19, pp. 327-335; Huikeshoven, F., Coleman, T.G., Jongsma, H.W., Mathematical model of the fetal cardiovascular system: The uncontrolled case (1980) Am J Physiol, 239, pp. R317-R325; Mielke, G., Benda, N., Cardiac output and central distribution of blood flow in the human fetus (2001) Circulation, 103, pp. 1662-1668; Cunningham, G., Leveno, K., MacDonald, P., Gilstrap III, L., Gant, N., Hankins, G., Clark, S., The morphological and functional development of the fetus (1996) Williams Obstetrics, pp. 151-190. , Cunningham G, Leveno K, MacDonald P, Gilstrap III L, Gant N, Hankins G, Clark S (eds) 20th Ed. Appleton & Lange, CT; Huikeshoven, F.J., Hope, I.D., Power, G.G., Gilbert, R.D., Longo, L.D., Mathematical model of fetal circulation and oxygen delivery (1985) Am J Physiol, 249, pp. R192-R202; Rasanen, J., Wood, D.C., Weiner, S., Ludomirski, A., Huhta, J.C., Role of the pulmonary circulation in the distribution of human fetal cardiac output during the second half of pregnancy (1996) Circulation, 94, pp. 1068-1073; Assali, N.S., Morris, J.A., Beck, R., Cardiovascular hemodynamics in the fetal lamb before and after lung expansion (1965) Am J Physiol, 208, pp. 122-129; Vilos, G.A., Liggins, G.C., Intrathoracic pressures in fetal sheep (1982) J Dev Physiol, 4, pp. 247-256; Hooper, S.B., Wallace, M.J., Role of the physicochemical environment in lung development (2006) Clin Exp Pharmacol Physiol, 33, pp. 273-279; Greenspan, J.S., Shaffer, T.H., Fox, W.W., Spitzer, A.R., Assisted ventilation: Physiologic implications and complications (1998) Fetal and Neonatal Physiology, 2. , Polin RA, Fox WW (eds) W.B. Saunders Company, Philadelphia, PA; Friedman, A.H., Fahey, J.T., The transitions from fetal to neonatal circulation: Normal responses and implications for infants with heart disease (1993) Semin Perinatol, 17, pp. 106-121; Ghanayem, N.S., Gordon, J.B., Modulation of pulmonary vasomotor tone in the fetus and neonate (2001) Respir Res, 2, pp. 139-144; Dawes, G.S., Mott, J.C., Widdicombe, J.G., Wyatt, D.G., Changes in the lungs of the new-born lamb (1953) J Physiol, 121, pp. 141-162; Brook, M.M., Heymann, M.A., Teitel, D.F., The heart (2001) Care of the High-Risk, , Klaus MH, Fanaroff AA (eds) 5th ed. W.B. Saunders Company, Philadelphia, PA; Gutyon, A.C., Fetal and neonatal physiology (1991) Textbook of Medical Physiology, , Guyton AC (ed) 8th ed. W.B. Saunders Company Philadelphia, PA; Lagercrantz, H., Bistoletti, P., Catecholamine release in the newborn infant at birth (1977) Pediatr Res, 11, pp. 889-893; Padbury, J.F., Diakomanolis, E.S., Hobel, C.J., Perelman, A., Fisher, D.A., Neonatal adaptation: Sympatho-adrenal response to umbilical cord cutting (1981) Pediatr Res, 15, pp. 1483-1487; Minoura, S., Gilbert, R.D., Postnatal change of cardiac function in lambs: Effects of ganglionic block and afterload (1987) J Dev Physiol, 9, pp. 123-135; Coskun, S., Yüksel, H., Bilgi, Y., Lacin, S., Tansug, N., Onag, A., Non-invasive evaluation of the adaptations of cardiac function in the neonatal period: A comparison of healthy infants delivered by vaginal route and caesarean section (2001) Acta Med Okayama, 55, pp. 213-218; Kishkurno, S., Takahashi, Y., Harada, K., Ishida, A., Tamura, M., Takada, G., Postnatal changes in left ventricular volume and contractility in healthy term infants (1997) Pediatric Cardiology, 18 (2), pp. 91-95. , DOI 10.1007/s002469900123; Shiota, T., Harada, K., Takada, G., Left ventricular systolic and diastolic function during early neonatal period using transthoracic echocardiography (2002) Tohoku J Exp Med, 197, pp. 151-158; Walther, F.J., Benders, M.J., Leighton, J.O., Early changes in the neonatal circulatory transition (1993) J Pediatr, 123, pp. 625-632; Hiraishi, S., Misawa, H., Oguchi, K., Kadoi, N., Saito, K., Fujino, N., Hojo, M., Yashiro, K., Two-dimensional Doppler echocardiographic assessment of closure of the ductus arteriosus in normal newborn infants (1987) J Pediatr, 111, pp. 755-760; Migliavacca, F., Dubini, G., Pennati, G., Pietrabissa, R., Fumero, R., Hsia, T.Y., De Leval, M.R., Computational model of the fluid dynamics in systemic-to-pulmonary shunts (2000) J Biomech, 33, pp. 549-557; Teitel, D.F., Iwamoto, H.S., Rudolph, A.M., Effects of birth-related events on central blood flow patterns (1987) Pediatr Res, 22, pp. 557-566; Anderson, D.F., Bissonnette, J.M., Faber, J.J., Thornburg, K.L., Central shunt flows and pressures in the mature fetal lamb (1981) Am J Physiol, 241, pp. H60-H66; Agata, Y., Hiraishi, S., Oguchi, K., Misawa, H., Horiguchi, Y., Fujino, N., Yashiro, K., Shimada, N., Changes in left ventricular output from fetal to early neonatal life (1991) J Pediatr, 119, pp. 441-445; Harada, K., Shiota, T., Takahashi, Y., Tamura, M., Takada, G., Changes in the volume and performance of the left ventricle in the early neonatal period (1994) Early Hum Dev, 39, pp. 201-209; Moss, A.J., Emmanouilides, G.C., Adams, F.H., Chuang, K., Response of ductus arteriosus and pulmonary and systemic arterial pressure to changes in oxygen environment in newborn infants (1964) Pediatrics, 33, pp. 937-944; Emmanouilides, G.C., Moss, A.J., Monset-Couchard, M., Marcano, B.A., Rzeznic, B., Cardiac output in newborn infants (1970) Biol Neonate, 15, pp. 186-197; Emmanouilides, G.C., Moss, A.J., Duffie Jr., E.R., Adams, F.H., Pulmonary arterial pressure changes in human newborn infants from birth to 3 days of age (1964) J Pediatr, 65, pp. 327-333; Soni, N., Williams, P., Positive pressure ventilation: What is the real cost? (2008) Br J Anaesth, 101, pp. 446-457; Moss, A.J., Emmanouilides, G.C., Duffie Jr., E.R., Closure of the ductus arteriosus in the newborn infant (1963) Pediatrics, 32, pp. 25-30
Keywords: article; artificial ventilation; biological model; birth; Blood flow; blood flow velocity; blood pressure; breathing; breathing mechanics; cardiovascular function; clamp; comparative study; Computer simulation; Constriction; education; evaluation; fetus; hemodynamics; human; Humans; Infant, Newborn; ligation; Models, Cardiovascular; newborn; Parturition; perinatal care; priority journal; Regional Blood Flow; reproducibility; Reproducibility of Results; Respiration, Artificial; Respiratory Mechanics; scientific literature; simulator; stimulation; time; Time Factors; umbilical cord; vascularization; vital sign

Monitoring incremental histogram distribution for change detection in data streams - Sebastião, R.; Gama, J.; Rodrigues, P.P.; Bernardes, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2010)
Histograms are a common technique for density estimation and they have been widely used as a tool in exploratory data analysis. Learning histograms from static and stationary data is a well known topic. Nevertheless, very few works discuss this problem when we have a continuous flow of data generated from dynamic environments. The scope of this paper is to detect changes from high-speed time-changing data streams. To address this problem, we construct histograms able to process examples once at the rate they arrive. The main goal of this work is continuously maintain a histogram consistent with the current status of the nature. We study strategies to detect changes in the distribution generating examples, and adapt the histogram to the most recent data by forgetting outdated data. We use the Partition Incremental Discretization algorithm that was designed to learn histograms from high-speed data streams. We present a method to detect whenever a change in the distribution generating examples occurs. The base idea consists of monitoring distributions from two different time windows: the reference window, reflecting the distribution observed in the past; and the current window which receives the most recent data. The current window is cumulative and can have a fixed or an adaptive step depending on the distance between distributions. We compared both distributions using Kullback-Leibler divergence, defining a threshold for change detection decision based on the asymmetry of this measure. We evaluated our algorithm with controlled artificial data sets and compare the proposed approach with nonparametric tests. We also present results with real word data sets from industrial and medical domains. Those results suggest that an adaptive window's step exhibit high probability in change detection and faster detection rates, with few false positives alarms. © 2010 Springer-Verlag Berlin Heidelberg.
Conference code: 81882Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-12519-5_2Language of Original Document: EnglishCorrespondence Address: Sebastião, R.; LIAAD, INESC Porto, L.A. Rua de Ceuta, 118, 6, Porto 4050-190, Portugal; email: raquel@liaad.up.ptReferences: Ayres-De-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis (2008) J. Perinat. Med., 36, pp. 260-264;Ayres-De-Campos, D., Bernardes, J., Garrido, A., Marques-De-Śa, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Matern Fetal Med., 9, pp. 311-318; Barbaŕa, D., Requirements for clustering data streams (2002) SIGKDD Explorations (Special Issue on Online, Interactive and Anytime Data Mining), 3 (2), pp. 23-27; Berthold, M., Hand, D., (1999) Intelligent Data Analysis-An Introduction., , Springer, Heidelberg; Breiman, L., (1993) Classification and Regression Trees., , Chapman & Hall, Boca Raton; Bock, R.K., Savicky, P., (2007) MAGIC Gamma Telescope Benchmark, , http://archive.ics.uci.edu/ml/datasets.html; Chabert, M., Ruiz, D., Tourneret, J.-Y., Optimal wavelet for abrupt change detection in multiplicative noise (2004) IEEE International Conference on Acoustics Speech and Signal Processing, pp. 1089-1092. , May 2004; Cormode, G., Garofalakis, M., Sketching probabilistic data streams (2007) Proceedings of the 2007 ACM SIGMOD International Conference on Management of Data, pp. 281-292. , June 2007; Correa, M., De, J., Raḿirez, M., Bielza, C., Pamies, J., Alique, J.R., Prediction of surface quality using probabilistic models (2007) 7th Congress of the Colombian Association of Automatic, Cali, Colombia, , March 21-24 Spanish; Dasu, T., Krishnan, S., Venkatasubramanian, S., Yi, K., An information-theoretic approach to detecting changes in multi-dimensional data streams (2006) Interface 2006, , Pasadena, CA Report; Gama, J., Medas, P., Castillo, G., Rodrigues, P.P., Learning with drift detection (2004) LNCS (LNAI), 3171, pp. 286-295. , Bazzan, A.L.C., Labidi, S. (eds.) Springer, Heidelberg SBIA 2004; Gama, J., Pinto, C., Discretization from data streams: Applications to histograms and data mining (2006) Proceedings of the 2006 ACM Symposium on Applied Computing, pp. 662-667; Goņcalves, H., Bernardes, J., Paula Rocha, J.A., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Human Development, 83 (9), pp. 585-591; Guha, S., Koudas, N., Woo, J., (2004) REHIST: Relative Error Histogram Construction Algorithms, pp. 300-311. , Proceedings of the VLDB Conference; Guha, S., Harb, B., Wavelet synopsis for data streams: Minimizing non-euclidean error (2005) Proceedings of the Eleventh ACM SIGKDD International Conference on Knowledge Discovery in Data Mining, pp. 88-97. , August 2005; Guha, S., Koudas, N., Shim, K., Approximation and streaming algorithms for histogram construction problems (2006) ACM Transactions on Database Systems (TODS), 31 (1), pp. 396-438; Hulten, G., Spencer, L., Domingos, P., Mining time-changing data streams (2001) Proceedings of the Seventh ACM SIGKDD International Conference on Knowledge Discovery and Data Mining ACM SIGKDD 2001, pp. 97-106. , ACM Press, New York; Jagadish, H.V., Koudas, N., Muthukrishnan, S., Poosala, V., Sevcik, K.C., Suel, T., Optimal histograms with quality guarantees (1998) Proc. of the VLDB Conference, pp. 275-286; Karras, P., Sacharidis, D., Mamoulis, N., Exploiting Duality in Summarization with Deterministic Guarantees. Approximating a Data Stream for Querying and Estimation: Algorithms and Performance Evaluation (2007) Proceedings of the ACM SIGKDD International Conference on Knowledge Discovery and Data Mining (KDD), pp. 380-389; Kifer, D., Ben-David, S., Gehrke, J., (2004) Detecting Change in Data Streams, pp. 180-191. , VLDB 2004: Proceedings of the 30th International Conference on Very Large Data Bases Morgan Kaufmann Publishers Inc., San Francisco; Klinkenberg, R., Renz, I., Adaptive information filtering: Learning in the presence of concept drifts (1998) Learning for Text Categorization, pp. 33-40. , AAAI Press, Menlo Park; Klinkenberg, R., Joachims, T., Detecting concept drift with support vector ma-chines (2000) Proceedings of ICML 2000, 17th International Conference on Machine Learning, Stanford, US, pp. 487-494. , Morgan Kaufmann Publishers, San Francisco; Klinkenberg, R., Learning drifting concepts: Example selection vs. example weight-ing (2004) Intelligent Data Analysis, 8 (3), pp. 281-300; Maloof, M., Michalski, R., Selecting examples for partial memory learning (2000) Machine Learning, 41, pp. 27-52; Pestana, D.D., Velosa, S.F., Introdu̧c̃aòa Probabilidadeèa Estat̀istica (2002) Funda̧c̃ao Calouste Gulbenkian; Pinto, C., Gama, J., Incremental discretization, application to data with concept drift (2007) Proceedings of the 2007 ACM Symposium on Applied Computing, pp. 467-468. , March 2007; Sebastĩao, R., Gama, J., Change detection in learning histograms from data streams (2007) Proceedings of Portuguese Conference on Artificial Intelligence, Guimar̃aes, Portugal, , December; Spinosa, E.J., Carvalho, A., Gama, J., OLINDDA: A cluster-based approach for detecting novelty and concept drift in data streams (2007) Proceedings of the 2007 ACM Symposium on Applied Computing, March 2007, pp. 448-452; Widmer, G., Kubat, M., Learning in the presence of concept drift and hidden contexts (1996) Machine Learning, 23, pp. 69-101
Keywords: Adaptive Cumulative Windows; Change detection; Data communication systems; Data reduction; Data stream; Data streams; Graphic methods; Learning histograms; Learning systems; Machine learning; Machine-learning; Monitoring; Monitoring data distribution; Sensors; signal detection; Statistical methods

Neuropeptide y and osteoblast differentiation - The balance between the neuro-osteogenic network and local control: Review Article - Franquinho, F.; Liz, M.A.; Nunes, A.F.; Neto, E.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
Accumulating evidence has contributed to a novel view in bone biology: bone remodeling, specifically osteoblast differentiation, is under the tight control of the central and peripheral nervous systems. Among other players in this neuro-osteogenic network, the neuropeptide Y (NPY) system has attracted particular attention. At the central nervous system level, NPY exerts its function in bone homeostasis through the hypothalamic Y2 receptor. Locally in the bone, NPY action is mediated by its Y1 receptor. Besides the presence of Y1, a complex network exists locally: not only there is input of the peripheral nervous system, as the bone is directly innervated by NPY-containing fibers, but there is also input from non-neuronal cells, including bone cells capable of NPY expression. The interaction of these distinct players to achieve a multilevel control system of bone homeostasis is still under debate. In this review, we will integrate the current knowledge on the impact of the NPY system in bone biology, and discuss the mechanisms through which the balance between central and the peripheral NPY action might be achieved. © 2010 FEBS.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1111/j.1742-4658.2010.07774.xPubMed ID: 20681986Language of Original Document: EnglishCorrespondence Address: Sousa, M. M.; IBMC, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: msousa@ibmc.up.ptChemicals/CAS: neuropeptide Y, 82785-45-3, 83589-17-7; Leptin; Neuropeptide Y; Protein Isoforms; Receptors, Neuropeptide YReferences: Bellido, T., Ali, A.A., Gubrij, I., Plotkin, L.I., Fu, Q., O'Brien, C.A., Manolagas, S.C., Jilka, R.L., Chronic elevation of parathyroid hormone in mice reduces expression of sclerostin by osteocytes: A novel mechanism for hormonal control of osteoblastogenesis (2005) Endocrinology, 146, pp. 4577-4583;Keller, H., Kneissel, M., SOST is a target gene for PTH in bone (2005) Bone, 37, pp. 148-158; O'Brien, C.A., Plotkin, L.I., Galli, C., Goellner, J.J., Gortazar, A.R., Allen, M.R., Robling, A.G., Turner, C.H., Control of bone mass and remodeling by PTH receptor signaling in osteocytes (2008) PLoS ONE, 3, p. 2942; Robling, A.G., Niziolek, P.J., Baldridge, L.A., Condon, K.W., Allen, M.R., Alam, I., Mantila, S.M., Harris, S.E., Mechanical stimulation of bone in vivo reduces osteocyte expression of Sost/sclerostin (2008) J Biol Chem, 283, pp. 5866-5875; Tatsumi, S., Ishii, K., Amizuka, N., Li, M., Kobayashi, T., Kohno, K., Ito, M., Ikeda, K., Targeted ablation of osteocytes induces osteoporosis with defective mechanotransduction (2007) Cell Metab, 5, pp. 464-475; McDonald, A.C., Schuijers, J.A., Shen, P.J., Gundlach, A.L., Grills, B.L., Expression of galanin and galanin receptor-1 in normal bone and during fracture repair in the rat (2003) Bone, 33, pp. 788-797; Pacifici, R., Cytokines, estrogen, and postmenopausal osteoporosis - The second decade (1998) Endocrinology, 139, pp. 2659-2661; You, L., Temiyasathit, S., Lee, P., Kim, C.H., Tummala, P., Yao, W., Kingery, W., Jacobs, C.R., Osteocytes as mechanosensors in the inhibition of bone resorption due to mechanical loading (2008) Bone, 42, pp. 172-179; Lerner, U.H., The role of skeletal nerve fibers in bone metabolism (2000) Endocrinologist, 10, pp. 377-382; Sherman, M.S., The nerves of bone (1963) J Bone Joint Surg Am, 45, pp. 522-528; Kuntz, A., Richins, C.A., Innervation of the bone marrow (1945) J Comp Neurol, 83, pp. 213-222; Miller, M.R., Kasahara, M., Observations on innervation of human long bones (1963) Anat Rec, 145, pp. 13-23; Thurston, T.J., Distribution of nerves in long bones as shown by silver impregnation (1982) J Anat, 134, pp. 719-728; Calvo, W., Fortezav, J., On development of bone marrow innervation in new-born rats as studied with silver impregnation and electron microscopy (1969) Am J Anat, 126, pp. 355-371; Sisask, G., Bjurholm, A., Ahmed, M., Kreicbergs, A., The development of autonomic innervation in bone and joints of the rat (1996) J Auton Nerv Syst, 59, pp. 27-33; Gajda, M., Litwin, J.A., Cichocki, T., Timmermans, J.P., Adriaensen, D., Development of sensory innervation in rat tibia: Co-localization of CGRP and substance P with growth-associated protein 43 (GAP-43) (2005) J Anat, 207, pp. 135-144; Jackman, A., Fitzgerald, M., Development of peripheral hindlimb and central spinal cord innervation by subpopulations of dorsal root ganglion cells in the embryonic rat (2000) J Comp Neurol, 418, pp. 281-298; Kosaras, B., Jakubowski, M., Kainz, V., Burstein, R., Sensory innervation of the calvarial bones of the mouse (2009) J Comp Neurol, 515, pp. 331-348; Jones, K.B., Mollano, A.V., Morcuende, J.A., Cooper, R.R., Saltzman, C.L., Bone and brain: A review of neural, hormonal, and musculoskeletal connections (2004) Iowa Orthop J, 24, pp. 123-132; Alberius, P., Skagerberg, G., Adrenergic innervation of the calvarium of the neonatal rat. Its relationship to the sagittal suture and developing parietal bones (1990) Anat Embryol (Berl), 182, pp. 493-498; Herskovits, M.S., Hallas, B.H., Singh, I.J., Study of sympathetic innervation of cranial bones by axonal transport of horseradish peroxidase in the rat: Preliminary findings (1993) Acta Anat (Basel), 147, pp. 178-183; Hill, E.L., Elde, R., Distribution of CGRP-, VIP-, D beta H-, SP-, and NPY-immunoreactive nerves in the periosteum of the rat (1991) Cell Tissue Res, 264, pp. 469-480; Kruger, L., Silverman, J.D., Mantyh, P.W., Sternini, C., Brecha, N.C., Peripheral patterns of calcitonin-gene-related peptide general somatic sensory innervation: Cutaneous and deep terminations (1989) J Comp Neurol, 280, pp. 291-302; Silverman, J.D., Kruger, L., Calcitonin-gene-related-peptide-immunoreactive innervation of the rat head with emphasis on specialized sensory structures (1989) J Comp Neurol, 280, pp. 303-330; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Robertson, S.A., Leinninger, G.M., Myers, Jr.M.G., Molecular and neural mediators of leptin action (2008) Physiol Behav, 94, pp. 637-642; Ahima, R.S., Flier, J.S., Leptin (2000) Annu Rev Physiol, 62, pp. 413-437; Tartaglia, L.A., Dembski, M., Weng, X., Deng, N., Culpepper, J., Devos, R., Richards, G.J., Deeds, J., Identification and expression cloning of a leptin receptor, OB-R (1995) Cell, 83, pp. 1263-1271; Zhang, Y., Proenca, R., Maffei, M., Barone, M., Leopold, L., Friedman, J.M., Positional cloning of the mouse obese gene and its human homologue (1994) Nature, 372, pp. 425-432; Takeda, S., Elefteriou, F., Levasseur, R., Liu, X., Zhao, L., Parker, K.L., Armstrong, D., Karsenty, G., Leptin regulates bone formation via the sympathetic nervous system (2002) Cell, 111, pp. 305-317; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Kriauciunas, A., The role of neuropeptide y in the antiobesity action of the obese gene product (1995) Nature, 377, pp. 530-532; Chronwall, B.M., Dimaggio, D.A., Massari, V.J., Pickel, V.M., Ruggiero, D.A., O'Donohue, T.L., The anatomy of neuropeptide-Y-containing neurons in rat brain (1985) Neuroscience, 15, pp. 1159-1181; Tatemoto, K., Carlquist, M., Mutt, V., Neuropeptide y - A novel brain peptide with structural similarities to peptide YY and pancreatic polypeptide (1982) Nature, 296, pp. 659-660; Pedrazzini, T., Pralong, F., Grouzmann, E., Neuropeptide Y: The universal soldier (2003) Cell Mol Life Sci, 60, pp. 350-377; Erickson, J.C., Hollopeter, G., Palmiter, R.D., Attenuation of the obesity syndrome of ob/ob mice by the loss of neuropeptide y (1996) Science, 274, pp. 1704-1707; Allison, S.J., Baldock, P.A., Herzog, H., The control of bone remodeling by neuropeptide y receptors (2007) Peptides, 28, pp. 320-325; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., Neuropeptide Y-, tyrosine hydroxylase- and vasoactive intestinal polypeptide-immunoreactive nerves in bone and surrounding tissues (1988) J Auton Nerv Syst, 25, pp. 119-125; Ahmed, M., Bjurholm, A., Kreicbergs, A., Schultzberg, M., Neuropeptide Y, tyrosine hydroxylase and vasoactive intestinal polypeptide-immunoreactive nerve fibers in the vertebral bodies, discs, dura mater, and spinal ligaments of the rat lumbar spine (1993) Spine, 18, pp. 268-273; Hill, E.L., Turner, R., Elde, R., Effects of neonatal sympathectomy and capsaicin treatment on bone remodeling in rats (1991) Neuroscience, 44, pp. 747-755; Lindblad, B.E., Nielsen, L.B., Jespersen, S.M., Bjurholm, A., Bunger, C., Hansen, E.S., Vasoconstrictive action of neuropeptide y in bone. The porcine tibia perfused in vivo (1994) Acta Orthop Scand, 65, pp. 629-634; Ahmad, T., Ugarph-Morawski, A., Li, J., Bileviciute-Ljungar, I., Finn, A., Ostenson, C.G., Kreicbergs, A., Bone and joint neuropathy in rats with type-2 diabetes (2004) Regul Pept, 119, pp. 61-67; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188; Bjurholm, A., Neuroendocrine peptides in bone (1991) Int Orthop, 15, pp. 325-329; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., Neuroendocrine regulation of cyclic AMP formation in osteoblastic cell lines (UMR-106-01, ROS 17/2.8, MC3T3-E1, and Saos-2) and primary bone cells (1992) J Bone Miner Res, 7, pp. 1011-1019; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Simmons, P., Greater bone formation of Y2 knockout mice is associated with increased osteoprogenitor numbers and altered Y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Nakamura, M., Sakanaka, C., Aoki, Y., Ogasawara, H., Tsuji, T., Kodama, H., Matsumoto, T., Noma, M., Identification of two isoforms of mouse neuropeptide Y-Y1 receptor generated by alternative splicing. Isolation, genomic structure, and functional expression of the receptors (1995) J Biol Chem, 270, pp. 30102-30110; Togari, A., Arai, M., Mizutani, S., Koshihara, Y., Nagatsu, T., Expression of mRNAs for neuropeptide receptors and beta-adrenergic receptors in human osteoblasts and human osteogenic sarcoma cells (1997) Neurosci Lett, 233, pp. 125-128; Igwe, J.C., Jiang, X., Paic, F., Ma, L., Adams, D.J., Baldock, P.A., Pilbeam, C.C., Kalajzic, I., Neuropeptide y is expressed by osteocytes and can inhibit osteoblastic activity (2009) J Cell Biochem, 108, pp. 621-630; Nunes, A.F., Liz, M.A., Franquinho, F., Teixeira, L., Sousa, V., Chenu, C., Lamghari, M., Sousa, M.M., Neuropeptide y expression and function during osteoblast differentiation - Insights from transthyretin knockout mice (2010) FEBS J, 277, pp. 263-275; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Invest, 109, pp. 915-921; Ducy, P., Schinke, T., Karsenty, G., The osteoblast: A sophisticated fibroblast under central surveillance (2000) Science, 289, pp. 1501-1504; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugmann, M., Li, M., Conditional deletion of hypothalamic Y2 receptors reverts gonadectomy-induced bone loss in adult mice (2006) J Biol Chem, 281, pp. 23436-23444; Clegg, D.J., Brown, L.M., Zigman, J.M., Kemp, C.J., Strader, A.D., Benoit, S.C., Woods, S.C., Geary, N., Estradiol-dependent decrease in the orexigenic potency of ghrelin in female rats (2007) Diabetes, 56, pp. 1051-1058; Zengin, A., Zhang, L., Herzog, H., Baldock, P.A., Sainsbury, A., Neuropeptide y and sex hormone interactions in humoral and neuronal regulation of bone and fat (2010) Trends Endocrinol Metab, 21, pp. 411-418; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29, pp. 1390-1395; Teixeira, L., Sousa, D.M., Nunes, A.F., Sousa, M.M., Herzog, H., Lamghari, M., NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors (2009) J Cell Biochem, 107, pp. 908-916; Sainsbury, A., Schwarzer, C., Couzens, M., Herzog, H., Y2 receptor deletion attenuates the type 2 diabetic syndrome of ob/ob mice (2002) Diabetes, 51, pp. 3420-3427; Wilding, J.P., Gilbey, S.G., Bailey, C.J., Batt, R.A., Williams, G., Ghatei, M.A., Bloom, S.R., Increased neuropeptide-Y messenger ribonucleic acid (mRNA) and decreased neurotensin mRNA in the hypothalamus of the obese (ob/ob) mouse (1993) Endocrinology, 132, pp. 1939-1944; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., Hypothalamic regulation of cortical bone mass: Opposing activity of Y2 receptor and leptin pathways (2006) J Bone Miner Res, 21, pp. 1600-1607; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., During, M.J., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Lee, N.J., Doyle, K.L., Sainsbury, A., Enriquez, R.F., Hort, Y.J., Riepler, S.J., Baldock, P.A., Herzog, H., Critical role for Y1 receptors in mesenchymal progenitor cell differentiation and osteoblast activity (2010) J Bone Miner Res, , doi:; Allison, S.J., Baldock, P.A., Enriquez, R.F., Lin, E., During, M., Gardiner, E.M., Eisman, J.A., Herzog, H., Critical interplay between neuropeptide y and sex steroid pathways in bone and adipose tissue homeostasis (2009) J Bone Miner Res, 24, pp. 294-304; Sainsbury, A., Baldock, P.A., Schwarzer, C., Ueno, N., Enriquez, R.F., Couzens, M., Inui, A., Gardiner, E.M., Synergistic effects of Y2 and Y4 receptors on adiposity and bone mass revealed in double knockout mice (2003) Mol Cell Biol, 23, pp. 5225-5233; Elefteriou, F., Takeda, S., Liu, X., Armstrong, D., Karsenty, G., Monosodium glutamate-sensitive hypothalamic neurons contribute to the control of bone mass (2003) Endocrinology, 144, pp. 3842-3847; Baldock, P.A., Lee, N.J., Driessler, F., Lin, S., Allison, S., Stehrer, B., Lin, E.J., Wong, I.P., Neuropeptide y knockout mice reveal a central role of NPY in the coordination of bone mass to body weight (2009) PLoS ONE, 4, p. 8415; Sainsbury, A., Cusin, I., Doyle, P., Rohner-Jeanrenaud, F., Jeanrenaud, B., Intracerebroventricular administration of neuropeptide y to normal rats increases obese gene expression in white adipose tissue (1996) Diabetologia, 39, pp. 353-356; Sainsbury, A., Herzog, H., Inhibitory effects of central neuropeptide y on the somatotropic and gonadotropic axes in male rats are independent of adrenal hormones (2001) Peptides, 22, pp. 467-471; Nunes, A.F., Saraiva, M.J., Sousa, M.M., Transthyretin knockouts are a new mouse model for increased neuropeptide y (2006) FASEB J, 20, pp. 166-168; Prigge, S.T., Mains, R.E., Eipper, B.A., Amzel, L.M., New insights into copper monooxygenases and peptide amidation: Structure, mechanism and function (2000) Cell Mol Life Sci, 57, pp. 1236-1259; Eipper, B.A., Stoffers, D.A., Mains, R.E., The biosynthesis of neuropeptides: Peptide alpha-amidation (1992) Annu Rev Neurosci, 15, pp. 57-85; Marques, F., Sousa, J.C., Oliveira, P., Oliveira, H.C., Palha, J.A., The absence of transthyretin does not impair regulation of lipid and glucose metabolism (2007) Horm Metab Res, 39, pp. 529-533
Keywords: Animals; Bone and Bones; bone cell; bone innervation; bone mass; cell differentiation; Homeostasis; Humans; immunoreactivity; leptin; Nerve Net; neuropeptide Y; neuropeptide Y receptor; neuropeptide Y2 receptor; nonhuman; NPY; NPY receptors; osteoblast; Osteoblasts; phenotype; priority journal; protein expression; protein interaction; Protein Isoforms; Receptors, Neuropeptide Y; review

Neuropeptide y expression and function during osteoblast differentiation - Insights from transthyretin knockout mice - Nunes, A.F.; Liz, M.A.; Franquinho, F.; Teixeira, L.; Sousa, V.; Chenu, C.; Lamghari, M.; Sousa, M.M. (FEBS JournalFEBS J., 2010)
To better understand the role of neuropeptide Y (NPY) in bone homeostasis, as its function in the regulation of bone mass is unclear, we assessed its expression in this tissue. By immunohistochemistry, we demonstrated, both at embryonic stages and in the adult, that NPY is synthesized by osteoblasts, osteocytes, and chondrocytes. Moreover, peptidylglycine α-amidating monooxygenase, the enzyme responsible for NPY activation by amidation, was also expressed in these cell types. Using transthyretin (TTR) KO mice as a model of augmented NPY levels, we showed that this strain has increased NPY content in the bone, further validating the expression of this neuropeptide by bone cells. Moreover, the higher amidated neuropeptide levels in TTR KO mice were related to increased bone mineral density and trabecular volume. Additionally, RT-PCR analysis established that NPY is not only expressed in MC3T3-E1 osteoblastic cells and bone marrow stromal cells (BMSCs), but is also detectable by RIA in BMSCs undergoing osteoblastic differentiation. In agreement with our in vivo observations, in vitro, TTR KO BMSCs differentiated in osteoblasts had increased NPY levels and exhibited enhanced competence in undergoing osteoblastic differentiation. In summary, this work contributes to a better understanding of the role of NPY in the regulation of bone formation by showing that this neuropeptide is expressed in bone cells and that increased amidated neuropeptide content is related to increased bone mass. © 2009 FEBS.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1111/j.1742-4658.2009.07482.xPubMed ID: 19954489Language of Original Document: EnglishCorrespondence Address: Sousa, M. M.; IBMC, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: msousa@ibmc.up.ptChemicals/CAS: neuropeptide Y, 82785-45-3, 83589-17-7; Amides; DNA Primers; Neuropeptide Y; Prealbumin; RNA, MessengerReferences: McDonald, A.C., Schuijers, J.A., Shen, P.J., Gundlach, A.L., Grills, B.L., Expression of galanin and galanin receptor-1 in normal bone and during fracture repair in the rat (2003) Bone, 33, pp. 788-797;Pacifici, R., Cytokines, estrogen, and postmenopausal osteoporosis - The second decade (1998) Endocrinology, 139, pp. 2659-2661; You, L., Temiyasathit, S., Lee, P., Kim, C.H., Tummala, P., Yao, W., Kingery, W., Jacobs, C.R., Osteocytes as mechanosensors in the inhibition of bone resorption due to mechanical loading (2008) Bone, 42, pp. 172-179; Chenu, C., Marenzana, M., Sympathetic nervous system and bone remodeling (2005) Joint Bone Spine, 72 (6), pp. 481-483. , DOI 10.1016/j.jbspin.2005.10.007, PII S1297319X05001661; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Invest, 109, pp. 915-921; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., During, M.J., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Elefteriou, F., Takeda, S., Liu, X., Armstrong, D., Karsenty, G., Monosodium glutamate-sensitive hypothalamic neurons contribute to the control of bone mass (2003) Endocrinology, 144, pp. 3842-3847; Elefteriou, F., Neuronal signaling and the regulation of bone remodeling (2005) Cell Mol Life Sci, 62, pp. 2339-2349; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., Neuropeptide Y-, tyrosine hydroxylase- and vasoactive intestinal polypeptide-immunoreactive nerves in bone and surrounding tissues (1988) J Auton Nerv Syst, 25, pp. 119-125; Hill, E.L., Elde, R., Distribution of CGRP-, VIP-, D beta H-, SP-, and NPY-immunoreactive nerves in the periosteum of the rat (1991) Cell Tissue Res, 264, pp. 469-480; Tabarowski, Z., Gibson-Berry, K., Felten, S.Y., Noradrenergic and peptidergic innervation of the mouse femur bone marrow (1996) Acta Histochem, 98, pp. 453-457; Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Simmons, P., Greater bone formation of y2 knockout mice is associated with increased osteoprogenitor numbers and altered y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Kriauciunas, A., The role of neuropeptide y in the antiobesity action of the obese gene product (1995) Nature, 377, pp. 530-532; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Allison, S., Baldock, P., Enriquez, R., Lin, E., During, M., Gardiner, E., Eisman, J., Herzog, H., Critical interplay between neuropeptide y and sex steroid pathways in bone and adipose tissue homeostasis (2008) J Bone Miner Res, 24, pp. 294-304; Nunes, A.F., Saraiva, M.J., Sousa, M.M., Transthyretin knockouts are a new mouse model for increased neuropeptide y (2006) FASEB J, 20, pp. 166-168; Mains, R.E., Cullen, E.I., May, V., Eipper, B.A., The role of secretory granules in peptide biosynthesis (1987) Ann NY Acad Sci, 493, pp. 278-291; Prigge, S.T., Mains, R.E., Eipper, B.A., Amzel, L.M., New insights into copper monooxygenases and peptide amidation: Structure, mechanism and function (2000) Cell Mol Life Sci, 57, pp. 1236-1259; Eipper, B.A., Stoffers, D.A., Mains, R.E., The biosynthesis of neuropeptides: Peptide alpha-amidation (1992) Annu Rev Neurosci, 15, pp. 57-85; Teixeira, L., Sousa, D.M., Nunes, A.F., Sousa, M.M., Herzog, H., Lamghari, M., NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors (2009) J Cell Biochem, 107, pp. 908-916; Amano, S., Arai, M., Goto, S., Togari, A., Inhibitory effect of NPY on isoprenaline-induced osteoclastogenesis in mouse bone marrow cells (2007) Biochim Biophys Acta, 1770, pp. 966-973; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., Hypothalamic regulation of cortical bone mass: Opposing activity of Y2 receptor and leptin pathways (2006) J Bone Miner Res, 21, pp. 1600-1607; Saper, C.B., Loewy, A.D., Swanson, L.W., Cowan, W.M., Direct hypothalamo-autonomic connections (1976) Brain Res, 117, pp. 305-312; Navia, J.M., Harris, S.S., Vitamin A influence on calcium metabolism and calcification (1980) Ann NY Acad Sci, 355, pp. 45-57; Wang, A., Ding, X., Sheng, S., Yao, Z., Retinoic acid inhibits osteogenic differentiation of rat bone marrow stromal cells (2008) Biochem Biophys Res Commun, 375, pp. 435-439; Takahashi, T., Kamiya, N., Kawabata, N., Takagi, M., The effect of retinoic acid on a zinc finger transcription factor, AJ18, during differentiation of a rat clonal preosteoblastic cell line, ROB-C20, into osteoblasts (2008) Arch Oral Biol, 53, pp. 87-94; Grouzmann, E., Comoy, E., Walker, P., Burnier, M., Bohuon, C., Waeber, B., Brunner, H., Production and characterization of four anti-neuropeptide y monoclonal antibodies (1992) Hybridoma, 11, pp. 409-424; Wei, S., Episkopou, V., Piantedosi, R., Maeda, S., Shimada, K., Gottesman, M.E., Blaner, W.S., Studies on the metabolism of retinol and retinol-binding protein in transthyretin-deficient mice produced by homologous recombination (1995) J Biol Chem, 270, pp. 866-870; Karga, H., Papapetrou, P.D., Korakovouni, A., Papandroulaki, F., Polymeris, A., Pampouras, G., Bone mineral density in hyperthyroidism (2004) Clin Endocrinol, 61, pp. 466-472; Episkopou, V., Maeda, S., Nishiguchi, S., Shimada, K., Gaitanaris, G.A., Gottesman, M.E., Robertson, E.J., Disruption of the transthyretin gene results in mice with depressed levels of plasma retinol and thyroid hormone (1993) Proc Natl Acad Sci USA, 90, pp. 2375-2379; Palha, J.A., Episkopou, V., Maeda, S., Shimada, K., Gottesman, M.E., Saraiva, M.J., Thyroid hormone metabolism in a transthyretin-null mouse strain (1994) J Biol Chem, 269, pp. 33135-33139; Palha, J.A., Hays, M.T., Morreale De Escobar, G., Episkopou, V., Gottesman, M.E., Saraiva, M.J., Transthyretin is not essential for thyroxine to reach the brain and other tissues in transthyretin-null mice (1997) Am J Physiol, 272, pp. 485-E493; Palha, J.A., Fernandes, R., De Escobar, G.M., Episkopou, V., Gottesman, M., Saraiva, M.J., Transthyretin regulates thyroid hormone levels in the choroid plexus, but not in the brain parenchyma: Study in a transthyretin-null mouse model (2000) Endocrinology, 141, pp. 3267-3272; Kingery, W.S., Offley, S.C., Guo, T.Z., Davies, M.F., Clark, J.D., Jacobs, C.R., A substance P receptor (NK1) antagonist enhances the widespread osteoporotic effects of sciatic nerve section (2003) Bone, 33, pp. 927-936; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29, pp. 1390-1395; Fleming, C.E., Saraiva, M.J., Sousa, M.M., Transthyretin enhances nerve regeneration (2007) J Neurochem, 103, pp. 831-839; Sainsbury, A., Cusin, I., Doyle, P., Rohner-Jeanrenaud, F., Jeanrenaud, B., Intracerebroventricular administration of neuropeptide y to normal rats increases obese gene expression in white adipose tissue (1996) Diabetologia, 39, pp. 353-356; Sainsbury, A., Herzog, H., Inhibitory effects of central neuropeptide y on the somatotropic and gonadotropic axes in male rats are independent of adrenal hormones (2001) Peptides, 22, pp. 467-471; Marques, F., Sousa, J.C., Oliveira, P., Oliveira, H.C., Palha, J.A., The absence of transthyretin does not impair regulation of lipid and glucose metabolism (2007) Horm Metab Res, 39, pp. 529-533; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Salingcarnboriboon, R., Tsuji, K., Komori, T., Nakashima, K., Ezura, Y., Noda, M., Runx2 is a target of mechanical unloading to alter osteoblastic activity and bone formation in vivo (2006) Endocrinology, 147, pp. 2296-2305
Keywords: 3T3 Cells; alpha amidating enzyme; Amidated neuropeptide; amidation; Amides; animal cell; animal tissue; Animals; article; Base Sequence; Bone Density; bone development; bone marrow cell; Bone Marrow Cells; Bone marrow stromal cells; bone mass; cartilage cell; cell differentiation; Cells, Cultured; Chondrocytes; controlled study; developmental stage; DNA Primers; embryo; embryo development; Homeostasis; immunohistochemistry; male; Mice; Mice, Knockout; mouse; Mus; neuropeptide Y; nonhuman; NPY; ossification; osteoblast; Osteoblastic differentiation; Osteoblasts; osteocyte; Osteocytes; peptide synthesis; prealbumin; priority journal; protein expression; protein function; radioimmunoassay; regulatory mechanism; reverse transcription polymerase chain reaction; RNA, Messenger; stroma cell; Stromal Cells; trabecular bone

Novel TiN-based dry EEG electrodes: Influence of electrode shape and number on contact impedance and signal quality - Fiedler, P.; Brodkorb, S.; Fonseca, C.; Vaz, F.; Zanow, F.; Haueisen, J. (IFMBE ProceedingsIFMBE Proc., 2010)
Usability of conventional wet electrodes for electroencephalography (EEG) is depending on a set of requirements, including time consuming and complex preparation of the skin of a subject, thus limiting possible application. A new class of "dry" electrodes without the need for electrolyte gels or pastes is being investigated. The dry application scenario of these novel electrodes requires a stable and reliable contact with the subject's skin. In order to develop an electrode shape with large contact surface for low electrode-skin impedance while also ensuring a sufficient hair layer penetration, several studies were performed. In this paper a distinct titanium electrode substrate shape for titanium nitride (TiN) coated electrodes was analyzed regarding influences of the number of interconnected electrodes and contact surface on electrodeskin impedance and biosignal quality. As a result 10 interconnected TiN pins had the lowest impedance values of 14 to 55 kΩ (depending on signal frequency) in comparison to 2 to 44 kΩ using conventional Ag/AgCl electrodes. Also the mean average deviation (MAD) of 5 seconds long EEG episodes were computed. The lowest MADs of 2.00 to 2.25 μV were determined using three interconnected TiN pins. In comparison to MADs of 2.13 to 2.54 μV, using a second set of Ag/AgCl electrodes, this leads to the conclusion that most of the error was related to spatial distance. This first step in optimization of electrode shape for dry TiN based electrodes showed very promising results and enable their use for EEG acquisition. © 2010 International Federation for Medical and Biological Engineering.
Conference code: 81753Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-13039-7_105Language of Original Document: EnglishCorrespondence Address: Fiedler, P.; Institute for Biomedical Engineering and Informatics, Ilmenau University of Technology, Gustav-Kirchhoff Str. 2, Ilmenau, Germany; email: patrique.fiedler@tu-ilmenau.deReferences: Taheri, B.A., Knight, R.T., Smith, R.L., A dry electrode for EEG recording (1994) Electroen Clin Neuro, 90, pp. 376-383;Searle, A., Kirkup, L., A direct comparison of wet, dry and insulating bioelectric recording electrodes (2000) Physiol Meas, 21, pp. 271-283; Ng, W.C., Seet, H.L., Lee, K.S., Micro-spike EEG electrode and vacuum-casting technology for mass production (2009) J Mater Process Tech, 209, pp. 4434-4438; Vaz, F., Ferreira, J., Ribeiro, E., Influence of nitrogen content on the structural, mechanical and electrical properties of TiN thin films (2005) Surf Coat Tech, 191, pp. 317-323; Cunha, L.T., Pedrosa, P., Tavares, C.J., The role of composition, morphology and crystalline structure in the electrochemical behavior of TiNx thin films for dry electrode sensor materials (2009) Electro-Chim Acta, 55, pp. 59-67; Jasper, H.H., The ten-twenty electrode system of the international federation (1958) Electroen Clin Neuro, 10, pp. 371-375; Haueisen, J., Leistritz, L., Süsse, T., Identifying mutual information transfer in the brain with diffenential-algebraic modeling: Evidence for fast oscillatory coupling between cortical somatosensory areas 3b and 1 (2007) NeuroImage, 37, pp. 130-136; Graichen, U., Witte, H., Haueisen, J., Analysis of induced components in electroencephalograms using a multiple correlation method (2009) BioMed Eng OnLine, 8, p. 21
Keywords: Ag/AgCl; Application scenario; Average deviation; Biochemical engineering; Bioelectric phenomena; bioelectric signals; biomedical electrodes; Biosignals; Coated electrodes; Coated wire electrodes; Contact impedance; Contact surface; electrochemical characterization; Electrochemical characterizations; Electrode shape; Electrode-skin impedance; Electrodes; electroencephalography; Electrophysiology; Medical computing; Signal frequencies; Signal quality; Spatial distance; Titanium; Titanium electrodes; Titanium nitride

Optical flow based Arabidopsis thaliana root meristem cell division detection - Quelhas, P.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2010)
The study of cell division and growth is a fundamental aspect of plant biology research. In this research the Arabidopsis thaliana plant is the most widely studied model plant and research is based on in vivo observation of plant cell development, by time-lapse confocal microscopy. The research herein described is based on a large amount of image data, which must be analyzed to determine meaningful transformation of the cells in the plants. Most approaches for cell division detection are based on the morphological analysis of the cells' segmentation. However, cells are difficult to segment due to bad image quality in the in vivo images. We describe an approach to automatically search for cell division in the Arabidopsis thaliana root meristem using image registration and optical flow. This approach is based on the difference of speeds of the cell division and growth processes (cell division being a much faster process). With this approach, we can achieve a detection accuracy of 96.4%. © 2010 Springer-Verlag.
Conference code: 81097Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-13775-4_22Language of Original Document: EnglishCorrespondence Address: Quelhas, P.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPPortugalReferences: Campilho, A., Garcia, B., Toorn, H.V.D., Wijk, H.V., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem (2006) Plant Journal, 48 (4), pp. 619-627. , DOI 10.1111/j.1365-313X.2006.02892.x;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res., 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A., Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo (2007) Motion'07, p. 13; Beemster, G.T.S., Baskin, T.I., Analysis of Cell Division and Elongation Underlying the Developmental Acceleration of Root Growth in Arabidopsis thaliana (1998) Plant Physiology, 116 (4), pp. 1515-1526; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation, classification, and tracking of cancer cell nuclei in time-lapse microscopy (2006) IEEE Trans. on Biomedical Engineering, 53 (4), pp. 762-766; Mao, K.Z., Zhao, P., Tan, P., Supervised learning-based cell image segmentation for p53 immunohistochemistry (2006) IEEE Trans. on Biomedical Engineering, 53 (6), pp. 1153-1163; Harder, N., M-Bermudez, F., Godinez, W., Ellenberg, J., Rohr, K., Automated analysis of mitotic cell nuclei in 3rd fluorescence microscopy image sequences Workshop on Bio-Image Inf.: Bio. Imag., Comp. Vision and Data Mining (2008); Yang, F., Mackey, M.A., Ianzini, F., Gallardo, G., Sonka, M., Cell segmentation, tracking, and mitosis detection using temporal context (2005) Medical Image Computing and Computer-Assisted Intervention (MICCAI), pp. 302-309; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., Automated arabidopsis plant root cell segmentation based on svm classification and region merging (2009) Comp. in Biology and Medicine, 39, pp. 785-793; Marcuzzo, M., Guichard, T., Quelhas, P., Maria Mendonça, A., Campilho, A., Cell division detection on the arabidopsis thaliana root (2009) LNCS, 5524, pp. 168-175. , Araujo, H., Mendonça, A.M., Pinho, A.J., Torres, M.I. (eds.) IbPRIA 2009. Springer, Heidelberg; Pereira, C.S., Mendonça, A.M., Campilho, A., Evaluation of contrast enhancement filters for lung nodule detection (2007) LNCS, 4633, pp. 878-888. , Kamel, M.S., Campilho, A. (eds.) ICIAR 2007. Springer, Heidelberg; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of arabidopsis thaliana root meristem in confocal microscopy (2004) LNCS, 3212, pp. 166-174. , Campilho, A.C., Kamel, M.S. (eds.) ICIAR 2004. Springer, Heidelberg; Hartley, R., Zisserman, A., (2003) Multiple View Geometry in Computer Vision, , Cambridge University Press, Cambridge; Lowe, D.G., Distinctive image features from scale-invariant keypoints (2004) International Journal of Computer Vision, 60, pp. 91-110; Brox, T., Bruhn, A., Papenberg, N., Weickert, J., High accuracy optical flow estimation based on a theory for warping (2004) LNCS, 3024, pp. 25-36. , Pajdla, T., Matas, J(G.) (eds.) ECCV 2004. Springer, Heidelberg
Keywords: Arabidopsis thaliana; Biology; Biology image processing; cell division detection; Cell divisions; cell proliferation; confocal microscopy; Detection accuracy; Growth process; Image data; Image quality; Image segmentation; Imaging systems; In-vivo; In-vivo images; Metadata; Morphological analysis; Optical data processing; Optical flows; Plant biology; Plant cells; research; Root meristem

Plasma surface modification of polycarbonate and poly(propylene) substrates for biomedical electrodes - Pedrosa, P.; Chappé, J.-M.; Fonseca, C.; Machado, A.V.; Nóbrega, J.M.; Vaz, F. (Plasma Processes and PolymersPlasma Processes Polym., 2010)
The effects of surface plasma treatments on the properties of PP and PC substrates were studied. Main results showed that the 0.48 Pa Ar treatment promoted the most favorable changes: roughness increased from 15 to 17 nm for PC and from 12 to 30 nm for PP, while the CA lowered from 95° to 59° and from 87° to 35° for PC and PP, respectively. The effects of the activation treatment on adhesion were checked by depositing a thin layer of TiN on both untreated and 0.48 Pa Ar plasma treated PC samples, and the adhesion to both substrates compared using the standard X-cut tape test. The Ar activated samples displayed better adhesion of the TiN film than the untreated ones, confirming the benefits of the surface changes induced by the plasma treatments. (Figure Presented) © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Cited By (since 1996): 4Export Date: 21 November 2012Source: Scopusdoi: 10.1002/ppap.200900176Language of Original Document: EnglishCorrespondence Address: Vaz, F.; Universidade do Minho, Centro de Fisica, Campus de Azurém, 4800-058 Guimarães, Portugal; email: fvaz@fisica.uminho.ptReferences: Moon, M.-W., Vaziri, A., (2009) Scripta Mater., 60, p. 44;Pandiyaraj, K., Selvarajan, V., Deshmukh, R.R., Gao, C., (2009) Appl. Surf. Sci., 255, p. 3965; Pandiyaraj, K., Selvarajan, V., Deshmukh, R.R., Gao, C., (2009) Vacuum, 83, p. 332; Tavares, C.J., Marques, S.M., Rebouta, L., Lanceros-Méndez, S., Sencadas, V., Costa, C.M., Alves, E., Fernandes, A.J., (2008) Thin Solid Films, 517, p. 1161; Eom, J.S., Kim, S.H., (2008) Thin Solid Films, 516, p. 4530; Di Mundo, R., De Benedictis, V., Palumbo, F., D'Agostino, R., (2009) Appl. Surf. Sci., 255, p. 5461; Özenbas, M., Tan, C., (1986) J. Cryst Growth, 78, p. 519; Goddard, J.M., Hotchkiss, J.H., (2007) Prog. Potym. Sci., 32, p. 698; Nathawat, R., Kumar, A., Kulshrestha, V., Vijay, Y.K., Kobayashi, T., Kanjilal, D., (2008) Nuel. Instrum. Methods Phys. Res. B, 266, p. 4749; Shin, Y.N., Kim, B.S., Ahn, H.H., Lee, J.H., Kim, K.S., Lee, J.Y., Kim, M.S., Lee, H.B., (2008) Appl. Surf. Sci., 255, p. 293; Lisboa, P., Gilliland, D., Ceccone, G., Valsesia, A., Rossi, F., (2006) Appl. Surf. Sci., 252, p. 4397; Muck, A., Svatos, A., (2007) Talanta, 74, p. 333; Sandoval-Paz, M.G., Ramirez-Bon, R., (2008) Thin Solid Films, 517, p. 6747; Park, S.K., Han, J.I., Kim, W.K., Kwak, M.G., (2001) Thin Solid Films, 397, p. 49; Pihan, S.A., Tsukruk, T., Förch, R., (2009) Surf. Coat. Technol., 13, p. 1856; Dayss, E., Leps, G., Meinhardt, J., (1999) Surf. Coat Teehnol., 116, p. 986; Pandiyaraj, K.N., Selvarajan, V., Deshmukh, R.R., Bousmina, M., (2008) Surf. Coat Teehnol., 202, p. 4218; Cheng, C., Liye, Z., Zhan, R.-J., (2006) Surf. Coat Teehnol., 200, p. 6659; Lai, J., Sunderland, B., Xue, J., Yan, S., Zhao, W., Folkard, M., Michael, B.D., Wang, Y., (2006) Appl. Surf. Sci., 252, p. 3375; Phenton, M.J., Lovell-Hoare, M.C., Stevens, G.C., (2001) J. Phys. D: Appl. Phys., 34, p. 2754; Ozeki, K., Hirakuri, K.K., (2008) Appl. Surf. Sci., 254, p. 1614; Vallon, S., Drévillon, B., Poncin-Epaillard, F., KlembergSapieha, J.E., Martinu, L., (1996) J. Vac. Sci. Teehnol. A, 14, p. 3194; Mirabedini, S.M., Arabi, H., Salem, A., Asiaban, S., (2007) Prog. Org. Coat., 60, p. 105; Kogelschatz, U., Elliason, B., Egli, W., (1999) Pure Appl. Chem., 71, p. 1819; Dorai, R., Kushner, M.J., (2003) J. Phys. D: Appl. Phys., 36, p. 666; Corval, G.J., Gray, D.G., Goring, D.A.I., (1976) J. Polym. Sci., Polym. Lett, 14, p. 231; Guimond, S., Radu, I., Czeremuszkin, G., Caisson, D.J., Wertheimer, M.R., (2002) Plasmas Polym., 7, p. 71; Guimond, S., Radu, I., Czeremuszkin, G., Wertheimer, M.R., (2002) Proc. 8th Int. Symp. High Pressure Low Temp. Plasma Chem., p. 400. , Pühajärve, Estland; Kogelschatz, U., Elliason, B., Egli, W., (1999) Pure Appl. Chem., 71, p. 1819; Cho, J.-S., Kim, K.-H., Han, S., Beag, Y.-W., Koh, S.-K., (2003) Prog. Org. Coat., 48, p. 251; Baek, J.-Y., An, J.-H., Choi, J.-M., Park, K.-S., Lee, S.-H., (2008) Sens. Actuators A, 143, p. 423; Gruetzmann, A., Hansen, S., Müller, J., (2007) Physiol Meas., 28, p. 1375; Ribeiro, E., Malczyk, A., Carvalho, S., Rebouta, L., Fernandes, I.V., Alves, E., Miranda, A.S., (2002) Surf. Coat. Teehnol, 151-152, p. 515; Sharma, R., Holcomb, E., Trigwell, S., Mazumder, M., (2007) J. Electrostat., 65, p. 269; Cunha, L.T., Pedrosa, P., J.Tavares, C., Alves, E., Vaz, F., Fonseca, C., (2009) Electrochim. Acta, 55, p. 59; Müller, D.J.M., Janovjak, H., Lehto, T., Kuerschner, L., Anderson, K., (2002) Prog. Biophys. Mol. Biol., 79, p. 1; Wolansky, G., Marmur, A., (1999) Colloids Surf. A, 156, p. 381; Mohamed, S.H., Kappertz, O., Ngaruiya, J.M., Niemeier, T., Drese, R., Wakkad, M., Wuttig, M., (2004) Phys. Stat. Sol., 202, p. 90; Carrino, L., Moroni, G., Polini, W., (2002) J. Mater. Proc. Technol., 121, p. 373
Keywords: Activation treatment; Adhesion; Ar plasmas; biomedical electrodes; Deposition; Electrodes; Functional polymers; Plasma surface modifications; Plasma treatment; Plasma treatments; Plasmas; Polymers; Propylene; Surface changes; Surface modification; Surface plasma treatment; Thin layers; TiN films; Titanium nitride

Proliferation and mineralization of bone marrow cells cultured on macroporous hydroxyapatite scaffolds functionalized with collagen type I for bone tissue regeneration - Teixeira, S.; Fernandes, M.H.; Ferraz, M.P.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
This study concerns the preparation and in vitro characterization of functionalized hydroxyapatite (HA) porous scaffolds, which are intended to be used as drug-delivery systems and bone-regeneration matrices. Hydroxyapatite scaffolds were prepared using the polymer replication method, and, after being submitted to a specific sintering cycle, collagen Type I was incorporated on the surface. After the coating procedure, collagen was crosslinked using the N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) conjugation method. In this study, hydroxyapatite scaffolds with uncrosslinked and cross-linked Type I collagen were evaluated. Cell morphology and deposition of extracellular matrix were assessed by scanning electron microscopy, whereas cell distribution was visualized by means of methylene blue staining. MTS and total DNA quantification assays were used to evaluate the viability and proliferation of human bone marrow cells cultured on all the materials for 28 days. Results showed that the cells were able to adhere, proliferate, and form a mineralized matrix on the surface of all the materials. Furthermore, the cells were able to spread from one pore to another and form cell clusters. The results show that these scaffolds are good candidates to serve as drug delivery vehicles and for tissue engineering purposes. © 2010 Wiley Periodicals, Inc.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32600Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; Divisão de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: sandra_teixeira3@yahoo.comChemicals/CAS: 1 (3 dimethylaminopropyl) 3 ethylcarbodiimide, 1892-57-5, 25952-53-8, 7084-11-9; DNA, 9007-49-2; hydroxyapatite, 1306-06-5, 51198-94-8; methylene blue, 61-73-4; n hydroxysuccinimide, 6066-82-6; Collagen Type I; Cross-Linking Reagents; DNA, 9007-49-2; Durapatite, 1306-06-5; Methylene Blue, 61-73-4Manufacturers: SigmarecticelReferences: Nair, M.B., Suresh Babu, S., Varma, H.K., John, A., A triphasic ceramic-coated porous hydroxyapatite for tissue engineering application (2008) Acta Biomaterialia, 4 (1), pp. 173-181. , DOI 10.1016/j.actbio.2007.07.004, PII S174270610700102X;Navarro, M., Ginebra, M.P., Planell, J.A., Zeppetelli, S., Ambrosio, L., Development and cell response of a new biodegradable composite scaffold for guided bone regeneration (2004) Journal of Materials Science: Materials in Medicine, 15 (4), pp. 419-422. , DOI 10.1023/B:JMSM.0000021113.88702.9d; Nishikawa, M., Myoui, A., Ohgushi, H., Ikeuchi, M., Tamai, N., Yoshikawa, H., Bone tissue engineering using novel interconnected porous hydroxyapatite ceramics combined with marrow mesenchymal cells: Quantitative and three-dimensional image analysis (2004) Cell Transplant, 13, pp. 367-376; Fredericks, D.C., Bobst, J.A., Petersen, E.B., Nepola, J.V., Dennis, J.E., Caplan, A.I., Burgess, A.V., Schulz, O.H., Cellular interactions and bone healing responses to a novel porous tricalcium phosphate bone graft material (2004) Orthopedics, 27 (1 SUPPL.), pp. s167-s173; Wang, Y., Uemura, T., Dong, J., Kojima, H., Tanaka, J., Tateishi, T., Application of Perfusion Culture System Improves in Vitro and in Vivo Osteogenesis of Bone Marrow-Derived Osteoblastic Cells in Porous Ceramic Materials (2003) Tissue Engineering, 9 (6), pp. 1205-1214. , DOI 10.1089/10763270360728116; Wilson, C.E., De Bruijn, J.D., Van Blitterswijk, C.A., Verbout, A.J., Dhert, W.J., Design and fabrication of standardized hydroxyapatite scaffolds with a defined macro-architecture by rapid prototyping for bone-tissue-engineering research (2004) J Biomed Mater Res, 68, pp. 123-132; Rice, J.M., Hunt, J.A., Gallagher, J.A., Quantitative evaluation of the biocompatible and osteogenic properties of a range of biphasic calcium phosphate (BCP) granules using primary cultures of human osteoblasts and monocytes (2003) Calcif Tissue Int, 72, pp. 726-736; Zheng, Q., Zhu, T., Du, J., Wang, H., Li, S., Studies on the ossification of compound transplantation of porous TCP ceramics and bone marrow (1996) J Tongji Med Univ, 16, pp. 236-240; Goshima, J., Goldberg, V.M., Caplan, A.I., The osteogenic potential of culture-expanded rat marrow mesenchymal cells assayed in vivo in calcium phosphate ceramic blocks (1991) Clin Orthop Relat Res, 262, pp. 298-311; Cheung, H.S., Haak, M.H., Growth of osteoblasts on porous calcium phosphate ceramic: An in vitro model for biocompatibility study (1989) Biomaterials, 10, pp. 63-67; Barrere, F., Van Blitterswijk, C.A., De Groot, K., Bone regeneration: Molecular and cellular interactions with calcium phosphate ceramics (2006) Int J Nanomedicine, 1, pp. 317-332; Grynpas, M.D., Pilliar, R.M., Kandel, R.A., Renlund, R., Filiaggi, M., Dumitriu, M., Porous calcium polyphosphate scaffolds for bone substitute applications in vivo studies (2002) Biomaterials, 23, pp. 2063-2070; Heilmann, F., Standard, O.C., Muller, F.A., Hoffman, M., Development of graded hydroxyapatite/CaCO(3) composite structures for bone ingrowth (2007) J Mater Sci, 18, pp. 1817-1824; Hsu, Y.H., Turner, I.G., Miles, A.W., Mechanical characterization of dense calcium phosphate bioceramics with interconnected porosity (2007) J Mater Sci, 18, pp. 2319-2329; Huang, X., Miao, X., Novel porous hydroxyapatite prepared by combining H 2O 2 foaming with PU sponge and modified with PLGA and bioactive glass (2007) Journal of Biomaterials Applications, 21 (4), pp. 351-374. , DOI 10.1177/0885328206063905; Ito, Y., Tanaka, N., Fujimoto, Y., Yasunaga, Y., Ishida, O., Agung, M., Ochi, M., Bone formation using novel interconnected porous calcium hydroxyapatite ceramic hybridized with cultured marrow stromal stem cells derived from Green rat (2004) J Biomed Mater Res A, 69, pp. 454-461; Li, S.H., De Wijn, J.R., Layrolle, P., De Groot, K., Synthesis of macroporous hydroxyapatite scaffolds for bone tissue engineering (2002) J Biomed Mater Res A, 61, pp. 109-120; Navarro, M., Del Valle, S., Martinez, S., Zeppetelli, S., Ambrosio, L., Planell, J.A., Ginebra, M.P., New macroporous calcium phosphate glass ceramic for guided bone regeneration (2004) Biomaterials, 25 (18), pp. 4233-4241. , DOI 10.1016/j.biomaterials.2003.11.012, PII S0142961203010780; Ramay, H.R.R., Zhang, M., Biphasic calcium phosphate nanocomposite porous scaffolds for load-bearing bone tissue engineering (2004) Biomaterials, 25 (21), pp. 5171-5180. , DOI 10.1016/j.biomaterials.2003.12.023, PII S0142961203011724; Wang, C., Kasuga, T., Nogami, M., Macroporous calcium phosphate glass-ceramic prepared by two-step pressing technique and using sucrose as a pore former (2005) JMater Sci, 16, pp. 739-744; Xin, R., Leng, Y., Chen, J., Zhang, Q., A comparative study of calcium phosphate formation on bioceramics in vitro and in vivo (2005) Biomaterials, 26 (33), pp. 6477-6486. , DOI 10.1016/j.biomaterials.2005.04.028, PII S0142961205003030; De Bruijn, J.D., Van Den Brink, I., Mendes, S., Dekker, R., Bovell, Y.P., Van Blitterswijk, C.A., Bone induction by implants coated with cultured osteogenic bone marrow cells (1999) Adv Dent Res, 13, pp. 74-81; De Groot, K., Effect of porosity and physicochemical properties on the stability, resorption, and strength of calcium phosphate ceramics (1988) Ann N Y Acad Sci, 523, pp. 227-233; De Groot, K., Wolke, J.G., Jansen, J.A., Calcium phosphate coatings for medical implants (1998) Proc Inst Mech Eng, 212, pp. 137-147; Van Blitterswijk, C.A., Grote, J.J., De Groot, K., Daems, W.T., Kuijpers, W., The biological performance of calcium phosphate ceramics in an infected implantation site. I. Biological performance of hydroxyapatite during Staphylococcus aureus infection (1986) J Biomed Mater Res, 20, pp. 989-1002; Arinzeh, T.L., Tran, T., Mcalary, J., Daculsi, G., A comparative study of biphasic calcium phosphate ceramics for human mesenchymal stem-cell-induced bone formation (2005) Biomaterials, 26 (17), pp. 3631-3638. , DOI 10.1016/j.biomaterials.2004.09.035, PII S0142961204008646; Kim, H.W., Knowles, J.C., Kim, H.E., Porous scaffolds of gelatin-hydroxyapatite nanocomposites obtained by biomimetic approach: Characterization and antibiotic drug release (2005) J Biomed Mater Res B Appl Biomater, 74, pp. 686-698; Legeros, R.Z., Properties of osteoconductive biomaterials: Calcium phosphates (2002) Clin Orthop Relat Res, 395, pp. 81-98; Mao, X.Z., Zhou, J.N., Hu, J.Z., Ruan, J.M., Wang, W.C., Ni, J.D., Hydroxyapatite/ tricalcium phosphate matrix scaffold as cell carriers in vitro (2004) Zhong Nan Da Xue Xue Bao Yi Xue Ban, 29, pp. 371-375; Rodriguez-Lorenzo, L.M., Vallet-Regi, M., Ferreira, J.M., Ginebra, M.P., Aparicio, C., Planell, J.A., Hydroxyapatite ceramic bodies with tailored mechanical properties for different applications (2002) J Biomed Mater Res A, 60, pp. 159-166; Tancred, D.C., Mccormack, B.A., Carr, A.J., A quantitative study of the sintering and mechanical properties of hydroxyapatite/ phosphate glass composites (1998) Biomaterials, 19, pp. 1735-1743; Rusnah, M., Andanastuti, M., Idris, B., The influence of sintering temperature on the porosity and strength of porous hydroxyapatite ceramics (2004) Med J Malaysia, 59 (SUPPL. B), pp. 158-159; Sanchez-Salcedo, S., Werner, J., Vallet-Regi, M., Hierarchical pore structure of calcium phosphate scaffolds by a combination of gel-casting and multiple tape-casting methods (2008) Acta Biomaterialia, 4, pp. 913-922; Teixeira, S., Ferraz, M.P., Monteiro, F.J., Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies (2008) J Mater Sci, 19, pp. 855-899; Gelse, K., Pöschl, E., Aigner, T., Collagens - Structure, function, and biosynthesis (2003) Adv Rev, 55, pp. 1531-1546; Friess, W., Collagen - Biomaterial for drug delivery (1998) Eur J Pharm Biopharm, 45, pp. 113-136; Weadock, K.S., Miller, E.J., Bellincampi, L.D., Zawadsky, J.P., Dunn, M.G., Physical crosslinking of collagen fibers: Comparison of ultraviolet irradiation and dehydrothermal treatment (1995) J Biomed Mater Res, 29, pp. 1373-1379; Yoshioka, S.A., Goissis, G., Thermal and spectrophotometric studies of new crosslinking method for collagen matrix with glutaraldehyde acetals (2008) Journal of Materials Science: Materials in Medicine, 19 (3), pp. 1215-1223. , DOI 10.1007/s10856-007-0151-0; Wissink, M.J., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H., Beugeling, T., Van Aken, W.G., Feijen, J., Binding and release of basic fibroblast growth factor from heparinized collagen matrices (2001) Biomaterials, 22, pp. 2291-2299; Wissink, M.J., Beernink, R., Pieper, J.S., Poot, A.A., Engbers, G.H., Beugeling, T., Van Aken, W.G., Feijen, J., Immobilization of heparin to EDC/NHS-crosslinked collagen. Characterization and in vitro evaluation (2001) Biomaterials, 22, pp. 151-163; Wissink, M.J., Beernink, R., Poot, A.A., Engbers, G.H., Beugeling, T., Van Aken, W.G., Feijen, J., Improved endothelialization of vascular grafts by local release of growth factor from heparinized collagen matrices (2000) J Control Release, 64, pp. 103-114; Wissink, M.J., Beernink, R., Scharenborg, N.M., Poot, A.A., Engbers, G.H., Beugeling, T., Van Aken, W.G., Feijen, J., Endothelial cell seeding of (heparinized) collagen matrices: Effects of bFGF pre-loading on proliferation (after low density seeding) and pro-coagulant factors (2000) J Control Release, 67, pp. 141-155; Wissink, M.J.B., Van Luyn, M.J.A., Beernink, R., Dijk, F., Poot, A.A., Engbers, G.H.M., Beugeling, T., Feijen, J., Endothelial cell seeding on crosslinked collagen: Effects of crosslinking on endothelial cell proliferation and functional parameters (2000) Thrombosis and Haemostasis, 84 (2), pp. 325-331; Teixeira, S., Oliveirał, S., Ferrazł, M.P., Monteiro, F.J., Three dimensional macroporous calcium phosphate scaffolds for bone tissue engineering (2008) Key Eng Mater, 361-363, pp. 947-950; Teixeira, S., Rodriguez, M., Pena, P., De Aza, A., De Aza, S., Ferraz, M., Monteiro, F., Physical characterization of hydroxyapatite porous scaffolds for tissue engineering (2009) Mater Sci Eng: C, 29, pp. 1510-1514
Keywords: 1 (3 dimethylaminopropyl) 3 ethylcarbodiimide; adult; Animal cell culture; Apatite; article; Automobile exhibitions; Bone; bone marrow cell; Bone Marrow Cells; bone matrix; bone mineralization; Bone Regeneration; bone tissue; Bone tissue regeneration; Calcification, Physiologic; cell adhesion; Cell clusters; Cell culture; Cell distribution; Cell morphology; cell proliferation; cell structure; cell viability; Cells, Cultured; cellular distribution; Ceramic materials; chemistry; Coating procedures; Collagen; collagen type 1; Collagen type I; conjugation; controlled study; cross linking; cross linking reagent; Cross-Linking Reagents; Crosslinked; cytology; Cytotoxicity; DNA; DNA quantification; drug conjugation; Drug delivery; drug delivery system; Drug delivery vehicles; drug effect; Drug-delivery systems; Durapatite; Extracellular matrices; extracellular matrix; Functionalized; human; Human bone marrow cells; human cell; Humans; hydroxyapatite; in vitro study; In-vitro; Macroporous; Macroporous ceramics; male; matrix; metabolism; methylene blue; Methylene blue staining; Microscopy, Electron, Scanning; molecular scaffold; n hydroxysuccinimide; N-hydroxysuccinimide; polymer; Polymer replication; porosity; Porous scaffold; Scaffolds; Scanning electron microscopy; Sintering; Sintering cycles; spectrometry; Spectrometry, X-Ray Emission; Tissue engineering; tissue scaffold; Tissue Scaffolds; Type I collagen; Young Adult

Protein matrices for improved wound healing: Elastase inhibition by a synthetic peptide model - Vasconcelos, A.; Pêgo, A.P.; Henriques, L.; Lamghari, M.; Cavaco-Paulo, A. (BiomacromoleculesBiomacromolecules, 2010)
The unique properties of silk fibroin were combined with keratin to develop new wound-dressing materials. Silk fibroin/keratin (SF/K) films were prepared to reduce high levels of elastase found on chronic wounds. This improved biological function was achieved by the incorporation of a small peptide synthesized based on the reactive-site loop of the Bowman-Birk Inhibitor (BBI) protein. In vitro degradation and release were evaluated using porcine pancreatic elastase (PPE) solution as a model of wound exudate. It was found that biological degradation and release rate are highly dependent on film composition. Furthermore, the level of PPE activity can be tuned by changing the film composition, thus showing an innovative way of controlling the elastase-antielastase imbalance found on chronic wounds. © 2010 American Chemical Society.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm100537bPubMed ID: 20690591Language of Original Document: EnglishCorrespondence Address: Vasconcelos, A.; Universidade Do Minho, Departamento de Engenharia Têxtil, Campus de Azurém, 4800-058 Guimarães, Portugal; email: andreiav@det.uminho.ptChemicals/CAS: Bowman Birk inhibitor, 37330-34-0; Fibroins, 9007-76-5; Keratins, 68238-35-7; Pancreatic Elastase, 3.4.21.36; Peptide Fragments; Trypsin Inhibitor, Bowman-Birk Soybean; Trypsin Inhibitors; fibroin, silkwormReferences: Boateng, J.S., Matthews, K.H., Stevens, H.N.E., Eccleston, G.M., Wound healing dressings and drug delivery systems: A review (2008) J. Pharm. Sci., 97, pp. 2892-2923;Rothe, M., Falanga, V., Growth factors: Their biology and promise in dermatologic diseases and tissue repair (1989) AMA Arch. Dermatol., 125, pp. 1390-1398; Shakespeare, P., Burn wound healing and skin substitutes (2001) Burns, 27, pp. 517-522; Martin, C.R., Wound infection: A failure of wound healing caused by an imbalance of bacteria (1997) Surg. Clin. North Am., 77, pp. 637-650; Stadelmann, W.K., Digenis, A.G., Tobin, G.R., Physiology and healing dynamics of chronic cutaneous wounds (1998) Am. J. Surg., 176, pp. 26S-38S; Eaglstein Wh, F.V., Chronic wounds (1997) Surg. Clin. North Am., 77, pp. 689-700; Gray, D.W.R., The wound exudate continuum: An aid to wound assessment (2004) Wounds U.K.: Appl. Wound Manageme. Suppl., pp. 19-21; Chen, W.Y.J., Rogers, A.A., Lydon, M.J., Characterization of biologic properties of wound fluid collected during early stages of wound healing (1992) J. Invest. Dermatol., 99, pp. 559-564; Brooke, B., Edward, J.C., Caroline, A.O., Leukocyte proteinases in wound healing: Roles in physiologic and pathologic processes (1999) Wound Repair Regener., 7, pp. 410-422; Dorne, R.Y., Benedict, C.N., The proteolytic environment of chronic wounds (1999) Wound Repair Regener., 7, pp. 433-441; Naomi, J.T., Michael, C.S., Shawn, M., Neil, B., Jane, G., Frank, B., Gillian, M., Gregory, S., Analysis of the acute and chronic wound environments: The role of proteases and their inhibitors (1999) Wound Repair Regener., 7, pp. 442-452; Enoch, S., Leaper, D.J., Basic science of wound healing (2008) Surgery (Oxford), 26, pp. 31-37; Chufa, H., Margaret, A.H., George, W.C., Frank, A., Effects of chronic wound fluid on the bioactivity of platelet-derived growth factor in serum-free medium and its direct effect on fibroblast growth (1999) Wound Repair Regener., 7, pp. 97-105; Chen, P., Rose, J., Love, R., Wei, C.H., Wang, B.C., Reactive sites of an anticarcinogenic Bowman-Birk proteinase inhibitor are similar to other trypsin inhibitors (1992) J. Biol. Chem., 267, pp. 1990-1994; Werner, M.H., Wemmer, D.E., Three-dimensional structure of soybean trypsin/chymotrypsin Bowman-Birk inhibitor in solution (1992) Biochemistry, 31, pp. 999-1010; Guangda, L.I.N., Wolfram, B., Robert, H., Chengwu, C.H.I., Richard, A.E., The 0.25-nm X-ray structure of the Bowman-Birk-type inhibitor from mung bean in ternary complex with porcine trypsin (1993) Eur. J. Biochem., 212, pp. 549-555; Voss, R.-H., Ulrich, E., Lars-Oliver, E., Gabriele, W., Young-Mi, K., Peter, F., Crystal structure of the bifunctional soybean Bowman-Birk inhibitor at 0.28-nm resolution (1996) Eur. J. Biochem., 242, pp. 122-131; Wolfram, B., Robert, H., Natural protein proteinase inhibitors and their interaction with proteinases (1992) Eur. J. Biochem., 204, pp. 433-451; Laskowski, M., Qasim, M.A., What can the structures of enzyme-inhibitor complexes tell us about the structures of enzyme substrate complexes (2000) Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 1477, pp. 324-337; McBride, J.D., Leatherbarrow, R.J., Synthetic peptide mimics of the Bowman-Birk inhibitor protein (2001) Curr. Med. Chem., 8, pp. 909-917; Jeffrey, D.M., Emma, M.W., Arnd, B.E.B., Agnès, M.J., Robin, J.L., Peptide mimics of the Bowman-Birk inhibitor reactive site loop (2002) Pept. Sci., 66, pp. 79-92; Vasconcelos, A., Freddi, G., Cavaco-Paulo, A., Biodegradable materials based on silk fibroin and keratin (2008) Biomacromolecules, 9, pp. 1299-1305; Ritger, P.L., Peppas, N.A., A simple equation for description of solute release II. Fickian and anomalous release from swellable devices (1987) J. Controlled Release, 5, pp. 37-42; Tanaka, H., Shimazu, T., Sugimoto, H., Yoshioka, T., Sugimoto, T., A sensitive and specific assay for granulocyte elastase in inflammatory tissue fluid using l-pyroglutamyl-l-prolyl-l-valine-p-nitroanilide (1990) Clin. Chim. Acta, 187, pp. 173-180; Yamauchi, K., Maniwa, M., Mori, T., Cultivation of fibroblast cells on keratin-coated substrata (1998) J. Biomater. Sci., Polym. Ed., 9, pp. 259-270; Li, M., Ogiso, M., Minoura, N., Enzymatic degradation behavior of porous silk fibroin sheets (2003) Biomaterials, 24, pp. 357-365; Minoura, N., Aiba, S., Higuchi, M., Gotoh, Y., Tsukada, M., Imai, Y., (1995) Biochem. Biophys. Res. Commun., 208, p. 511; Yamauchi, K., Hojo, H., Yamamoto, Y., Tanabe, T., Enhanced cell adhesion on RGDS-carrying keratin film (2003) Mater. Sci. Eng., C, 23, pp. 467-472; Roh, D.-H., Kang, S.-Y., Kim, J.-Y., Kwon, Y.-B., Young Kweon, H., Lee, K.-G., Park, Y.-H., Lee, J.-H., Wound healing effect of silk fibroin/alginate-blended sponge in full thickness skin defect of rat (2006) J. Mater. Sci.: Mater. Med., 17, pp. 547-552; Lu, S., Wang, X., Lu, Q., Hu, X., Uppal, N., Omenetto, F.G., Kaplan, D.L., Stabilization of Enzymes in Silk Films (2009) Biomacromolecules, 10, pp. 1032-1042; Hofmann, S., Wong Po Foo, C.T., Rossetti, F., Textor, M., Vunjak-Novakovic, G., Kaplan, D.L., Merkle, H.P., Meinel, L., Silk fibroin as an organic polymer for controlled drug delivery (2006) J. Controlled Release, 111, pp. 219-227; Numata, K., Cebe, P., Kaplan, D.L., Mechanism of enzymatic degradation of beta-sheet crystals (2010) Biomaterials, 31, pp. 2926-2933; Shudong, W., Youzhu, Z., Guibo, Y., Hongwei, W., Zhihui, D., Electrospun polylactide/silk fibroin-gelatin composite tubular scaffolds for small-diameter tissue engineering blood vessels (2009) J. Appl. Polym. Sci., 113, pp. 2675-2682; Motta, A., Migliaresi, C., Faccioni, F., Torricelli, P., Fini, M., Giardino, R., Fibroin hydrogels for biomedical applications: Preparation, characterization and in vitro cell culture studies (2004) J. Biomater. Sci., Polym. Ed., 15, p. 851; Bondar, B., Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Functionality of endothelial cells on silk fibroin nets: Comparative study of micro-and nanometric fibre size (2008) Biomaterials, 29, pp. 561-572; Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Outgrowth endothelial cells isolated and expanded from human peripheral blood progenitor cells as a potential source of autologous cells for endothelialization of silk fibroin biomaterials (2006) Biomaterials, 27, pp. 5399-5408; Unger, R.E., Wolf, M., Peters, K., Motta, A., Migliaresi, C., James Kirkpatrick, C., Growth of human cells on a non-woven silk fibroin net: A potential for use in tissue engineering (2004) Biomaterials, 25, pp. 1069-1075; Huang, Y., Yu, H., Xiao, C., PH-sensitive cationic guar gum/poly(acrylic acid) polyelectrolyte hydrogels: Swelling and in vitro drug release (2007) Carbohydr. Polym., 69, pp. 774-783; Edwards, J.V., Alvin, F.B., Sarah, B., Abul, J.U., Kelman, C.I., Robert, F.D., Steven, J.M., Inhibition of elastase by a synthetic cotton-bound serine protease inhibitor: In vitro kinetics and inhibitor release (1999) Wound Repair Regener., 7, pp. 106-118; Schneider, A., Wang, X.Y., Kaplan, D.L., Garlick, J.A., Egles, C., Biofunctionalized electrospun silk mats as a topical bioactive dressing for accelerated wound healing (2009) Acta Biomater., 5, pp. 2570-2578; Gariani, T., McBride, J.D., Leatherbarrow, R.J., The role of the P2′ position of Bowman-Birk proteinase inhibitor in the inhibition of trypsin: Studies on P2′ variation in cyclic peptides encompassing the reactive site loop (1999) Biochim. Biophys. Acta, Protein Struct. Mol. Enzymol., 1431, pp. 232-237; Zablotna, E., Kazmierczak, K., Jaskiewicz, A., Stawikowski, M., Kupryszewski, G., Rolka, K., Chemical synthesis and kinetic study of the smallest naturally occurring trypsin inhibitor SFTI-1 isolated from sunflower seeds and its analogues (2002) Biochem. Biophys. Res. Commun., 292, pp. 855-859
Keywords: animal cell; Animals; article; Atomic force microscopy; Biodegradation; Biological degradation; Biological functions; biomaterial; Bombyx; Bowman Birk inhibitor; Bowman-Birk inhibitors; cell proliferation; Chronic wounds; controlled study; Cytotoxicity test; Degradation; Elastase; elastase inhibitor; enzyme activity; Enzyme inhibition; Fibroins; Film composition; In-vitro; keratin; Keratins; mass spectrometry; materials testing; Mice; Microscopy, Atomic Force; NIH 3T3 Cells; nonhuman; pancreatic elastase; Peptide Fragments; Peptides; priority journal; protein binding; Protein matrices; Release rate; Silk; Silk fibroin; Spectrometry, Mass, Electrospray Ionization; Sus; Swine; Synthetic peptide; Trypsin Inhibitor, Bowman-Birk Soybean; Trypsin Inhibitors; wound fluid; Wound healing

Receptor-mediated gene delivery using PAMAM dendrimers conjugated with peptides recognized by mesenchymal stem cells - Santos, J.L.; Pandita, D.; Rodrigues, J.; Pêgo, A.P.; Granja, P.L.; Balian, G.; Tomás, H. (Molecular PharmaceuticsMol. Pharm., 2010)
As mesenchymal stem cells (MSCs) can differentiate into multiple cell types, the delivery of exogenous genes to this type of cell can be an important tool in tissue regeneration and engineering. However transfection of MSCs using nonviral gene delivery vectors is difficult, the development of more efficient and safe DNA vehicles being necessary. Moreover, specific transfection of MSCs may be required to avoid unwanted side effects in other tissues. In this study, a novel family of gene delivery vectors based on poly(amidoamine) (PAMAM) dendrimers functionalized with peptides displaying high affinity toward MSCs was prepared. The vectors were characterized with respect to their ability to neutralize, bind and compact plasmid DNA (pDNA). The complexes formed between the vectors and pDNA were analyzed concerning their size, -potential, capacity of being internalized by cells and transfection efficiency. These new vectors exhibited low cytotoxicity, receptor-mediated gene delivery into MSCs and transfection efficiencies superior to those presented by native dendrimers and by partially degraded dendrimers. © 2010 American Chemical Society.
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1021/mp9002877PubMed ID: 20230026Language of Original Document: EnglishCorrespondence Address: Balian, G.; Orthopaedic Research Laboratories, Department of Orthopaedics and Biochemistry and Molecular Genetics, University of Virginia Health System, Charlottesville, VA 22908, United States; email: lenat@uma.ptChemicals/CAS: Dendrimers; Green Fluorescent Proteins, 147336-22-9; PAMAM Starburst; Peptides; enhanced green fluorescent proteinReferences: Väänänen, H.K., Mesenchymal stem cells (2005) Ann. Med., 37, pp. 469-479;Caplan, A.I., Adult mesenchymal stem cells for tissue engineering versus regenerative medicine (2007) J. Cell Physiol., 213, pp. 341-347; Kay, M.A., Glorioso, J.C., Naldini, L., Viral vectors for gene therapy: The art of turning infectious agents into vehicles of therapeutics (2001) Nat. Med., 7, pp. 33-40; Mastrobattista, E., Bravo, S.A., Van Der Aa, M., Crommelin, D.J.A., Nonviral gene delivery systems: From simple transfection agents to artificial viruses (2005) Drug Discovery Today: Technol., 2, pp. 103-109; Merdan, T., Kopecek, J., Kissel, T., Prospects for cationic polymers in gene and oligonucleotide therapy against cancer (2002) Adv. Drug Delivery Rev., 54, pp. 715-758; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8, pp. 235-245; McMahon, J.M., Conroy, S., Lyons, M., Greiser, U., O'Shea, C., Strappe, P., Howard, L., O'Brien, T., Gene transfer into rat mesenchymal stem cells: A comparative study of viral and nonviral vectors (2006) Stem Cells Dev., 15, pp. 87-96; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Delivery Rev., 57, pp. 2106-2129; Duf-s, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Delivery Rev., 57, pp. 2177-2202; Guillot, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31, pp. 1111-1127; Smith, D.K., Dendrimers and the double helix-from DNA binding towards gene therapy (2008) Curr. Top. Med. Chem., 8, pp. 1187-1203; Kukowska-Latallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker Jr., J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U.S.A., 93, pp. 4897-4902; Santos, J.L., Oramas, E., Pêgo, A.P., Granja, P.L., Tomás, H., Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors (2009) J. Controlled Release, 134, pp. 141-148; Balian, G., (2008), Bone Targeting Peptides. In United States Patent 7,323,542, issued January 29Snyder, S.L., Sobocinski, P.Z., An improved 2,4,6-trinitrobenzenesulfonic acid method for the determination of amines (1975) Anal. Biochem., 64, pp. 284-288; Haensler, J., Szoka Jr., F.C., Polyamidoamine cascade polymers mediate efficient transfection of cells in culture (1993) Bioconjugate Chem., 4, pp. 372-379; Hosseinkhani, H., Yamamoto, M., Inatsugu, Y., Hiraoka, Y., Inoue, S., Shimokawa, H., Tabata, Y., Enhanced ectopic bone formation using a combination of plasmid DNA impregnation into 3-D scaffold and bioreactor perfusion culture (2006) Biomaterials, 27, pp. 1387-1398; Perrot, S., Dutertre-Catella, H., Martin, C., Rat, P., Warnet, J.M., Resazurin metabolism assay is a new sensitive alternative test in isolated pig cornea (2003) Toxicol. Sci., 72, pp. 122-129; Wood, K.C., Little, S.R., Langer, R., Hammond, P.T., A family of hierarchically self-assembling linear-dendritic hybrid polymers for highly efficient targeted gene delivery (2005) Angew. Chem., Int. Ed., 44, pp. 6704-6708; Dan Luo, K.H., Belcheva, N., Han, E., Mark Saltzman, W., Poly(ethylene glycol)-conjugated PAMAM dendrimer for biocompatible, high-efficiency dna delivery (2002) Macromolecules, 35, pp. 3456-3462; Schaffer, D.V., Lauffenburger, D.A., Optimization of cell surface binding enhances efficiency and specificity of molecular conjugate gene delivery (1998) J. Biol. Chem., 273, pp. 28004-28009; Santos, J.L., Oliveira, H., Pandita, D., Pêgo, A.P., Granja, P.L., Tomás, H., Functionalization of poly(amidoamine) dendrimers with hydrophobic chains for improved gene delivery in mesenchymal stem cells (2010) J. Controlled Release, , doi: 10.1016/j.jconrel.2010.01.034
Keywords: animal cell; animal experiment; animal tissue; Animals; article; asparaginylserylmethionylisoleucylalanylhistidylasparaginyllysylthreonylarginylmethionylhistidylglycylglycylglycylserylcysteine; Cell recognition; cell survival; Cells, Cultured; controlled study; Cytotoxicity; dendrimer; Dendrimers; DNA; DNA binding; Electrophoresis, Agar Gel; flow cytometry; Gene delivery; gene targeting; Gene Transfer Techniques; gene vector; genetic transfection; Genetic Vectors; Green Fluorescent Proteins; male; Mesenchymal stem cell; Mesenchymal Stem Cells; Models, Theoretical; multigene family; nonhuman; PAMAM dendrimers; peptide; Peptides; plasmid DNA; polyamidoamine; priority journal; rat; Rats; Rats, Wistar; serylglycylhistidylglutaminylleucylleucylleucylasparaginyllysylmethionylprolylasparaginylglycylglycylglycylserylcysteine; unclassified drug; Zeta potential

Segmentation of the carotid intima-media region in B-mode ultrasound images - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Image and Vision ComputingImage Vision Comput, 2010)
This paper proposes a new approach for the segmentation of both near-end and far-end intima-media regions of the common carotid artery in ultrasound images. The method requires minimal user interaction and is able to segment the near-end wall in arteries with large, hypoechogenic and irregular plaques, issues usually not considered previously due to the increased segmentation difficulty. The adventitia is detected by searching for the best fit of a cubic spline to edges having features compatible with the adventitia boundary. The algorithm uses a global smoothness constraint and integrates discriminating features of the adventitia to reduce the attraction by other edges. Afterwards, using the information of the adventitia location, the lumen boundary is detected by combining dynamic programming, smooth intensity thresholding surfaces and geometric snakes. Smooth contours that correctly adapt to the intima are produced, even in the presence of deep concavities. Moreover, unlike balloon-based snakes, the propagation force does not depend on gradients and does not require a predefined direction. An extensive statistical evaluation is computed, using a set of 47 images from 24 different symptomatic patients, including several classes, sizes and shapes of plaques. Bland-Altman plots of the mean intima-media thickness, for manual segmentations of two medical experts, show a high intra-observer and inter-observer agreement, with mean differences close to zero (mean between -0.10 mm and 0.18 mm) and with the large majority of differences within the limits of agreement (standard deviation between 0.10 mm and 0.12 mm). Similar plots reveal a good agreement between the automatic and the manual segmentations (mean between -0.07 mm and 0.11 mm and standard deviation between 0.11 mm and 0.12 mm). © 2009 Elsevier B.V. All rights reserved.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: IVCODdoi: 10.1016/j.imavis.2009.09.017Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Inst. de Eng. Biomédica, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, Portugal; email: rhr@isep.ipp.ptReferences: O'Leary, D., Polak, J., Kronmal, R., Manolio, T., Burke, G., Wolfson Jr., S., Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults (1999) New Engl. J. Med., 340, pp. 14-22;Hodis, H., Mack, W., LaBree, L., Selzer, R., Liu, C., Liu, C., Azen, S., The role of carotid arterial intima-media thickness in predicting clinical coronary events (1998) Ann. Intern. Med., 128 (4), pp. 262-269; Kern, R., Szabo, K., Hennerici, M., Meairs, S., Characterization of carotid artery plaques using real-time compound B-mode ultrasound (2004) Stroke, 35, pp. 870-875; Ellis, S.M., Naoumova, R.P., Neuwirth, C.K., Eckersley, R., Cosgrove, D.O., Thompson, G.R., Sidhu, P.S., Measurement of the reflectivity of the intima-medial layer of the common carotid artery improves the discriminatory value of intima-medial thickness measurement as a predictor of risk of atherosclerotic disease (2007) Ultrasound Med. Biol., 33 (7), pp. 1029-1038; Graf, I.M., Schreuder, F.H.B.M., Hameleers, J.M., Mess, W.H., Reneman, R.S., Hoeks, A.P.G., Wall irregularity rather than intima-media thickness is associated with nearby atherosclerosis (2009) Ultrasound Biol. Med., 35 (6), pp. 955-961; Baldassarre, D., Amato, M., Bondioli, A., Sirtori, C.R., Tremoli, E., Carotid artery intima-media thickness measured by ultrasonography in normal clinical practice correlates well with atherosclerosis risk factors (2000) Stroke, 31, pp. 2426-2430; Halenka, M., Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography (1999) Acta Univ. Palacki. Olomu. Fac. Med., 142, pp. 7-12; Rocha, R., (2007) Image Segmentation and Reconstruction of 3D Surfaces from Carotid Ultrasound Images, , http://www.ineb.fe.up.pt/bmivic, Ph.D. thesis, Faculdade de Engenharia da Universidade do Porto, Porto July; Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24 (4-5), pp. 757-777; Sonka, M., Liang, W., Stefancik, R., Stolpen, A., Handbook of Medical Imaging: Medical Image Processing and Analysis (2000) SPIE, 2; Yu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Process., 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Process., 13 (12), pp. 1640-1655; Thijssen, J.M., Ultrasonic speckle formation, analysis and processing applied to tissue characterization (2003) Pattern Recogn. Lett., 24 (4-5), pp. 659-675; Loizou, C.P., Pattichis, C.S., Christodoulou, C.I., Istepanian, R.S.H., Pantziaris, M., Nicolaides, A., Comparative evaluation of despeckle filtering in ultrasound imaging of the carotid artery (2005) IEEE Trans. Ultrason. Fer. Freq. Control, 52 (10), pp. 1653-1669; Chan, K.L., Ultrasonic tissue characterization using fractal feature (1993) IEE Conf. Acoustic Sensing and Imaging, 369, pp. 183-188; Touboul, P.J., Prati, P., Scarabin, P.-Y., Adrai, V., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertens., 10 (5), pp. 37-41; Gariepy, J., Massonneau, M., Levenson, J., Heudes, D., Simon, A., the Groupe de prevention cardio-vasculaire en medecine du travail, evidence for in vivo carotid and femoral wall thickness in human hypertension (1993) J. Hypertens., 22 (1), pp. 111-118; Selzer, R.H., Hodis, H.N., Kwong-Fu, H., Mack, W.J., Lee, P.L., Liu, C.R., Liu, C.H., Evaluation of computerized edge tracking for quantifying intima-media thickness of the common carotid artery from B-mode ultrasound images (1994) Atherosclerosis, 111, pp. 1-11; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Comput. Cardiol.; Wendelhag, I., Liang, Q., Gustavsson, T., Wikstrand, J., A new automated computerized analyzing system simplifies readings and reduces the variability in ultrasound measurement of intima-media thickness (1997) Stroke, 28, pp. 2195-2200; Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound Bmode images using snakes, in: International Conference on Image Analysis and Processing, B. Werer, 1999, pp. 452-457Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imag., 19 (2), pp. 127-142; Selzer, R.H., Mack, W.J., Lee, P.L., Kwong-Fu, H., Hodis, H.N., Improved common carotid elasticity and intima-media thickness measurements from computer analysis of sequential ultrasound frames (2001) Atherosclerosis, 154 (1), pp. 185-193; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clin. Physiol., 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Comput. Methods Programs Biomed., 67, pp. 27-37; Stein, J.H., Korcarz, C.E., Mays, M.E., Douglas, P.S., Palta, M., Zhang, H., LeCaire, T., Fan, L., A semiautomated ultrasound border detection program that facilitates clinical measurement of ultrasound carotid intima-media thickness (2005) J. Am. Soc. Echocardiogr., 18 (3), pp. 244-251; Loizou, C.P., Pattichis, C.S., Pantziaris, M., Tyllis, T., Nicolaides, A., Snakes based segmentation of the common carotid artery intima media (2007) Med. Bio. Eng. Comput., 45, pp. 35-49; Yanowitz, S.D., Bruckstein, A.M., A new method for image segmentation (1989) Comput. Graph. Image Process., 46, pp. 82-95; Chan, T., Vese, L., Active contours without edges (2001) IEEE Trans. Image Process., 10 (2), pp. 266-277; Vese, L.A., Chan, T.F., A multiphase level set framework for image segmentation using the Mumford and Shah model (2002) Int. J. Comput. Vision, 50 (3), pp. 271-293; Fischler, M.A., Bolles, R.C., Random sample consensus: a paradigm for model fitting with applications to image analysis and automated cartography (1981) Commun. ACM, 24 (6), pp. 381-395; Zack, G.W., Rogers, W.E., Latt, S.A., Automatic measurement of sister chromatid exchange frequency (1977) J. Histochem. Cytochem., 25 (7), pp. 741-753; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Anal. Mach. Intell., 8 (6), pp. 679-698; Rudin, L., Osher, S., Fatemi, E., Nonlinear total variation based noise removal algorithms (1992) Proceedings of the Eleventh Annual International Conference of the Center for Nonlinear Studies on Experimental Mathematics: Computational Issues in Nonlinear Science, pp. 259-268. , Elsevier North-Holland, Inc; Rudin, L., Osher, S., Total variation based image restoration with free local constraints (1994) Proceedings of IEEE International Conference on Image Processing (ICIP'94), 1, pp. 31-35; Sethian, J.A., (1999) Level Set Methods and Fast Marching Methods, , Cambridge University Press; Osher, S., Fedkiw, R., (2003) Level Set Methods and Dynamic Implicit Surfaces, , Springer-Verlag, New York; Mumford, D., Shah, J., Optimal approximations by piecewise smooth functions and associated variational problems (1989) Commun. Pure Appl. Math., 42 (5), pp. 577-685; Burden, R., Faires, J.D., (2000) Numerical Analysis, , Brooks Cole; Breu, H., Gil, J., Kirkpatrick, D., Werman, M., Linear time Euclidean distance transform algorithms (1995) IEEE Trans. Pattern Anal. Mach. Intell., 17 (5), pp. 529-533; Bland, J.M., Altman, D.G., Statistical methods for assessing agreement between two methods of clinical measurement (1986) Lancet, 1 (8476), pp. 307-310; Loizou, C.P., Pattichis, C.S., Pantziaris, M., Nicolaides, A., An integrated system for the segmentation of atherosclerotic carotid plaque (2007) IEEE Trans. Info. Tech. Biomed., 11 (6), pp. 661-667; de Boor, C., (1978) A Practical Guide to Splines, , Springer-Verlag; Unser, M., Splines: a perfect fit for signal and image processing (1999) IEEE Signal Processing Magazine, 16 (6), pp. 22-38; Yang, Z., Tuthill, T.A., Raunig, D.L., Fox, M.D., Analoui, M., Pixel compounding: resolution-enhanced ultrasound imaging for quantitative analysis (2007) Ultrasound Med. Biol., 33 (8), pp. 1309-1319
Keywords: Acoustic waves; B-mode ultrasound images; Best fit; Carotid; Common carotid artery; Cubic spline; Digital image storage; Dynamic programming; Edge detection; End-wall; Function evaluation; Geometric snake; Geometric snakes; Image segmentation; Intima-media thickness; Manual segmentation; Medical experts; New approaches; Smoothness constraints; Standard deviation; Statistical evaluation; statistics; Thresholding; Ultrasonics; Ultrasound image; Ultrasound images; User interaction

Simulation for teaching normal delivery and shoulder dystocia to midwives in training - Reynolds, A.; Ayres-de-Campos, D.; Pereira-Cavaleiro, A.; Ferreira-Bastos, L. (Education for Health: Change in Learning and PracticeEduc. Health, 2010)
Introduction and objective: The cognitive impact of using simulation sessions in midwifery training has not been the subject of previous research. The aim of this study was to compare the effect on students' knowledge of a simulation session versus an image-based lecture, for teaching routine management of normal delivery and resolution of shoulder dystocia to midwives in training. Methods: Sixty students were enrolled three weeks after a "labour and delivery" class, and randomly assigned to two groups. Ten were subsequently excluded as they were not able to attend the whole session and/or did not complete the tests. In the simulation group (n=26), students were divided into pairs and attended a 30-minute hands-on session in the simulation centre. In the lecture group (n=24), students participated in a 30-minute image-based interactive lecture. A ten-question multiple-choice test was taken before (pre-test) and after (post-test) both sessions, to evaluate students' knowledge of labour and delivery and shoulder dystocia. Learner satisfaction was evaluated by adding a six question Likert scale questionnaire to the post-test. Independent t-test, paired samples t-test, and Mann-Whitney test were used for statistical analysis, setting significance at p<0.05. Results: The simulation group showed a significantly higher mean post-test score (6.38 vs. 5.16; p=0.003) and a significantly greater inter-test score progression (p<0.0001). Overall learner satisfaction was also higher in this group (p=0.0001). Conclusions: A significantly higher short-term reinforcement of knowledge and greater learner satisfaction was obtained using simulation sessions compared to image-based lectures when teaching routine management of normal delivery and resolution of shoulder dystocia to midwives in training. © A Reynolds, D Ayres-de-Campos, A Pereira-Cavaleiro, L Ferreira-Bastos, 2010.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: EDHEFLanguage of Original Document: EnglishCorrespondence Address: Reynolds, A.; Simulation Centre, Department of Obstetrics and Gynaecology, Faculty of Medicine, University of PortoPortugalReferences: Wilford, A., Doyle, T.J., Integrating simulation training into the nursing curriculum (2006) British Journal of Nursing, 15 (17), pp. 926-930;Lichtman, R., Walker, D., Supporting Innovations in Midwifery Education (2003) Journal of Midwifery & Women's Health, 48 (6), pp. 389-390; Johnson, P.G., Fullerton, J.T., Midwifery education models. A Contemporary Review (1998) Journal of Nurse-Midwifery, 43 (5), pp. 351-357; Lathrop, A., Winningham, B., van de Vusse, L., Simulation-Based Learning for Midwives: Background and Pilot Implementation (2007) Journal of Midwifery & Women's Health, 52, pp. 492-498; Murray, C., Grant, M.J., Howarth, M.L., Leigh, J., The use of simulation as a teaching and learning approach to support practice learning (2008) Nurse Education in Practice, 8, pp. 5-8; Council of Deans for Health. Simulation and Practice Learning Project: Outcome of a pilot study to the test principles for auditing simulated practice learning environments in the pre-registration nursing programme (2007) Final Report, , http://www.webcitation.org/5am8HXGA3, Nursing and Midwifery Council (NMC), Retrieved April 6, 2010 from, (Archived by WebCite®); Jeffries, P.R., A Framework for Designing, Implementing and Evaluating Simulations Used as Teaching Strategies in Nursing (2005) Nursing Education Perspectives, 26 (2), pp. 96-103; McCallum, J., The debate in favour of using simulation education in pre-registration adult nursing (2007) Nurse Education Today, 27, pp. 825-831; Morgan, R., Using clinical skills laboratories to promote theory-practice integration during first practice placement: An Irish perspective (2006) Journal of Clinical Nursing, 15, pp. 155-161; Issenberg, S.B., McGaghie, W.C., Hart, I.R., Mayer, J.W., Felner, J.M., Petrusa, E.R., Waugh, R.A., Ewy, G.A., Simulation Technology for Health Care Professional Skills Training and Assessment (1999) Journal of the American Medical Association, 282 (9), pp. 861-866; Gardner, R., Raemer, D.B., Simulation in Obstetrics and Gynecology (2008) Obstetrics and Gynecology Clinics of North America, 35, pp. 97-127; LeFlore, J.L., Anderson, M., Michael, J.L., Engle, W.D., Anderson, J.D., Comparison of Self-Directed Learning Versus Instructor-Modeled Learning During a Simulated Clinical Experience (2007) Simulation in Healthcare, 2, pp. 170-177; Seybert, A.L., Barton, C.M., Simulation-Based Learning to Teach Blood Pressure Assessment to Doctor of Pharmacy Students (2007) American Journal of Pharmaceutical Education, 71 (3), pp. 1-6; Hoffmann, R.L., O'Donnell, J.M., Kim, Y., The Effects of Human Patient Simulators on Basic Knowledge in Critical Care Nursing with Undergraduate Senior Baccalaureate Nursing Students (2007) Simulation in Healthcare, 2, pp. 110-114; Shepherd, I.A., Kelly, C.M., Skene, F.M., White, K.T., Enhancing Graduate Nurses' Health Assessment Knowledge and Skills Using Low-fidelity Adult Human Simulation (2007) Simulation in Healthcare, 2, pp. 16-24; Reynolds, A., Ayres-de-Campos, D., Bastos, L.F., van Meurs, W.L., J. B. Impact of Labor and Delivery Simulation Classes in Undergraduate Medical Learning (2008) Medical Education Online, 13, p. 14; Seropian, M., Dillman, D., Lasater, K., Gavilanes, J., Mannequin-Based Simulation to Reinforce Pharmacology Concepts (2007) Simulation in Healthcare, 2, pp. 218-223; Cioffi, J., Purcal, N., Arundell, F., A Pilot Study to Investigate the Effect of a Simulation Strategy on the Clinical Decision Making of Midwifery Students (2005) The Journal of Nursing Education, 44 (3), pp. 131-134; Robertson, B., An Obstetric Simulation Experience in an Undergraduate Nursing Curriculum (2006) Nurse Educator, 31 (2), pp. 74-78
Keywords: Labour and delivery; Midwifery training; Patient simulators; Shoulder dystocia

The stability of self-assembled monolayers with time and under biological conditions - Maciel, J.; Martins, M.C.L.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
The stability of self-assembled monolayers (SAMs) of different functionalities (CH 3
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32746PubMed ID: 20336761Language of Original Document: EnglishCorrespondence Address: Barbosa, M. A.; Divisão de Biomateriais, INEB - Instituto de Engenharia Biomédica, Universidade do Porto, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: mbarbosa@ineb.up.ptChemicals/CAS: sulfur, 13981-57-2, 7704-34-9; Culture Media; Ethanol, 64-17-5; Sulfhydryl Compounds; Sulfur, 7704-34-9; Water, 7732-18-5References: Mrksich, M., Whitesides, G.M., Using self-assembled monolayers to understand the interactions of man- Made surfaces with proteins and cells (1996) Annual Review of Biophysics and Biomolecular Structure, 25, pp. 55-78;Mrksich, M., Dike, L.E., Tien, J., Ingber, D.E., Whitesides, G.M., Using microcontact printing to pattern the attachment of mammalian cells to self-assembled monolayers of alkanethiolates on transparent films of gold and silver (1997) Exp Cell Res, 235, pp. 305-313; Flynn, N.T., Tran, T.N.T., Cima, M.J., Langer, R., Long-term stability of self-assembled monolayers in biological media (2003) Langmuir, 19, pp. 10909-10915; Willey, T.M., Vance, A.L., Van Buuren, T., Bostedt, C., Terminello, L.J., Fadley, C.S., Rapid degradation of alkanethiol-based self-assembled monolayers on gold in ambient laboratory conditions (2005) Surf Sci, 576, pp. 188-196; Jones, J.A., Qin, L.A., Meyerson, H., Kwon, I.K., Matsuda, T., Anderson, J.M., Instability of self-assembled monolayers as a model material system for macrophage/FBGC cellular behavior (2008) J Biomed Mater Res Part A, 86 A, pp. 261-268; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- And methyl-terminated alkanethiols self-assembled monolayers (2003) Journal of Biomedical Materials Research - Part a, 67 (1), pp. 158-171; Martins, M.C.L., Fonseca, C., Barbosa, M.A., Ratner, B.D., Albumin adsorption on alkanethiols self-assembled monolayers on gold electrodes studied by chronopotentiometry (2003) Biomaterials, 24, pp. 3697-3706; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Sastry, M., A note on the use of ellipsometry for studying the kinetics of formation of self-assembled monolayers (2000) Bull Mater Sci, 23, pp. 159-163; Castner, D.G., Hinds, K., Grainger, D.W., X-ray photoelectron spectroscopy sulfur 2p study of organic thiol and disulfide binding interactions with gold surfaces (1996) Langmuir, 12, pp. 5083-5086; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., Spontaneously organized molecular assemblies. 4. Structural characterization of n-alkyl thiol monolayers on gold by optical ellipsometry, infrared spectroscopy, and electrochemistry (1987) J Am Chem Soc, 109, pp. 3559-3568; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Goncalves, I.C., Martins, M.C., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) J Biomed Mater Res A, 89, pp. 642-653; Martins, M.C.L., Curtin, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res Part A, 88 A, pp. 162-173; Chidsey, C.E.D., Loiacono, D.N., Chemical functionality in self-assembled monolayers: Structural and electrochemical properties (1990) Langmuir, 6, pp. 682-691; Martins, M.C., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on cibacron blue F3G-A immobilized onto oligo(ethylene glycol)- Terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14, pp. 945-954; Ahn, H.S., Cuong, P.D., Park, S., Kim, Y.W., Lim, J.C., Effect of molecular structure of self-assembled monolayers on their tribological behaviors in nano- and microscales (2003) Wear, 255, pp. 819-825; Barrias, C.C., Martins, C.L., Miranda, C.S., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: Effect of surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; Martins, M.C., Fonseca, C., Barbosa, M.A., Ratner, B.D., Albumin adsorption on alkanethiols self-assembled monolayers on gold electrodes studied by chronopotentiometry (2003) Biomaterials, 24, pp. 3697-3706; Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-terminated self-assembled monolayers (2005) Biomaterials, 26, pp. 3891-3899; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res A, 65, pp. 429-434; Cavalleri, O., Gonella, G., Terreni, S., Vignolo, M., Pelori, P., Floreano, L., Morgante, A., Rolandi, R., High resolution XPS of the S 2p core level region of the L-cysteine/gold interface (2004) J Phys: Condens Matter, 16, pp. S2477; Petrovykh, D.Y., Kimura-Suda, H., Opdahl, A., Richter, L.J., Tarlov, M.J., Whitman, L.J., Alkanethiols on platinum: Multicomponent selfassembled monolayers (2006) Langmuir, 22, pp. 2578-2587; Rieley, H., Price, N.J., Smith, T.L., Yang, S.H., Photo-oxidation and photo-reduction in alkylthiol monolayers self-assembled on gold (1996) J Chem Soc Faraday Trans, 92, pp. 3629-3634; Raiber, K., Terfort, A., Benndorf, C., Krings, N., Strehblow, H.-H., Removal of self-assembled monolayers of alkanethiolates on gold by plasma cleaning (2005) Surf Sci, 595, pp. 56-63; Molina, R., Espinos, J.P., Yubero, F., Erra, P., Gonzalez-Elipe, A.R., XPS analysis of down stream plasma treated wool: Influence of the nature of the gas on the surface modification of wool (2005) Appl Surf Sci, 252, pp. 1417-1429; Love, J.C., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1170; Allara, D.L., Critical issues in applications of self-assembled monolayers (1995) Biosens Bioelectron, 10, pp. 771-783; Horn, A.B., Russell, D.A., Shorthouse, L.J., Simpson, T.R.E., Ageing of alkanethiol self-assembled monolayers (1996) J Chem Soc Faraday Trans, 92, pp. 4759-4762; Li, Y., Huang, J., McIver, R.T., Hemminger, J.C., Characterization of thiol self-assembled films by laser desorption Fourier transform mass spectrometry (1992) J Am Chem Soc, 114, pp. 2428-2432; Schoenfisch, M.H., Pemberton, J.E., Air stability of alkanethiol self-assembled monolayers on silver and gold surfaces (1998) J Am Chem Soc, 120, pp. 4502-4513; Mani, G., Johnson, D.M., Marton, D., Dougherty, V.L., Feldman, M.D., Patel, D., Ayon, A.A., Agrawal, C.M., Stability of self-assembled monolayers on titanium and gold (2008) Langmuir, 24, pp. 6774-6784; Tarlov, M.J., Newman, J.G., Static secondary ion mass spectrometry of self-assembled alkanethiol monolayers on gold (1992) Langmuir, 8, pp. 1398-1405; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Huang, J., Dahlgren, D.A., Hemminger, J.C., Photopatterning of self-assembled alkanethiolate monolayers on gold: A simple monolayer photoresist utilizing aqueous chemistry (1994) Langmuir, 10, pp. 626-628
Keywords: Animals; article; Binding energy; Biological conditions; Biological studies; Body fluids; Cattle; Cell culture; Culture Media; Ethanol; Female; Fetal bovine serum; In-cell; materials testing; measurement; molecular stability; Nitrogen chamber; nonhuman; Organic polymers; Oxidation; Oxidation-Reduction; Oxidized sulfur; Photodegradation; Photoelectron spectroscopy; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Stability; Storage condition; Sulfhydryl Compounds; Sulfur; Surface Properties; Water; wettability; X ray photoelectron spectroscopy; XPS; XPS spectra

Synthesis and characterization of HAp nanorods from a cationic surfactant template method - Coelho, J.M.; Moreira, J.A.; Almeida, A.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2010)
Hydroxyapatite (HAp) [Ca 10(PO 4) 6(OH) 2] nanorods were synthesized using a surfactant templating method, with cetyltrimethylammonium bromide (CTAB) micelles acting as template for HAp growth. The effects of the sintering temperature on the morphological and crystallographic characteristics and on chemical composition of the "as-prepared" structures are discussed. The experimental results show that low heat-treatment temperatures are preferred in order to obtain high quality nanorods, with diameters ranging between 20 and 50 nm. High heat-treatment temperatures enhance the thermal decomposition of HAp into other calcium phosphate compounds, and the sintering of particles into micrometer ball-like structures. The stability of aqueous suspensions of HAp nanorods is also discussed. © 2010 Springer Science+Business Media, LLC.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-010-4122-5PubMed ID: 20623177Language of Original Document: EnglishCorrespondence Address: Moreira, J. A.; IFIMUP, IN-Institute of Nanoscience and Nanotechnology, Universidade Do Porto, Rua do Campo Alegre 687, Porto 4169-007, Portugal; email: jamoreir@fc.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Cations; Cetrimonium Compounds; Surface-Active Agents; cetrimonium, 6899-10-1References: Rao, C.N.R., Cheetham, A.K., Materials science at the nanoscale (2006) Nanomaterials Handbook, pp. 1-2. , Y. Gogotsi (eds). CRC Press, Taylor & Francis Group New York;Guo, Y., Shi, D., Lian, J., Zdw, W., Cho, H., Liu, G., Quantum dot conjugated hydroxylapatite nanoparticles for in vivo imaging (2008) Nanotechnology, 19, 6p. , 175102; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Production of porous hydroxyapatite with potential for controlled drug delivery (2004) Mater Sci Forum, 455-456, pp. 358-360. , 10.4028/www.scientific.net/MSF.455-456.358; Vallet-Regi, M., Ceramics for medical applications (2001) Journal of the Chemical Society, Dalton Transactions, (2), pp. 97-108. , DOI 10.1039/b007852m; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angewandte Chemie - International Edition, 41 (17), pp. 3130-3146. , DOI 10.1002/1521-3773(20020902)41:17<3130::AID-ANIE3130>3.0.CO;2-1; Ferraz, M.P., Monteiro, F.J., Manuel, C.M., Hydroxyapatite nanoparticles: A review of preparation methodologies (2004) J Appl Biomater Biomech, 2, pp. 74-80. , 1:CAS:528:DC%2BD2cXnvFWiurk%3D; Cengiz, B., Gokce, Y., Yildiz, N., Aktas, Z., Calimi, A., Synthesis and characterization of hydroxyapatite nanoparticles (2008) Colloids Surf A Physichochem Eng Aspects, 322, pp. 29-33. , 1:CAS:528:DC%2BD1cXmt1OqtbY%3D 10.1016/j.colsurfa.2008.02.011; Ying, J.Y., Mehnert, P.C., Wong, M.S., Synthesis and application of supramolecular-templated mesoporous materials (1999) Angew Chem Int Ed, 38, pp. 56-77. , 1:CAS:528:DyaK1MXpsValtg%3D%3D 10.1002/(SICI)1521-3773(19990115)38:1/ 2<56::AID-ANIE56>3.0.CO;2-E; Cates, M.E., Fielding, S.M., Rheology of giant micelles (2006) Advances in Physics, 55 (7-8), pp. 799-879. , DOI 10.1080/00018730601082029, PII T6J4U87W3G5RTN2J; Nagarajan, R., Molecular thermodynamics of giant micelles (2007) Giant Micelles-properties and Applications, pp. 2-5. , R. Zana E.W. Kaler (eds). CRC Pess, Taylor & Francis Group New York; Li, Y., Tjandra, W., Tam, K.C., Synthesis of nanoporous hydroxyapatite using cationic surfactants as templates (2008) Mater Res Bull, 43, pp. 2318-2326. , 1:CAS:528:DC%2BD1cXnsVSrtr4%3D 10.1016/j.materresbull.2007.08.008; Yao, J., Tjandra, W., Chen, Y.Z., Tam, K.C., Mab, J., Soh, B., Hydroxyapatite nanostructure material derived using cationic surfactant as a template (2003) J Mater Chem, 13, pp. 3053-3057. , 1:CAS:528:DC%2BD3sXptlemsro%3D 10.1039/b308801d; Berret, J.F., Rheology of wormlike micelles: Equilibrium properties and shear banding transition (2006) Molecular Gels. Materials with Self-assembled Fibrillar Networks, pp. 667-720. , R.G. Weiss P. Terech (eds). Springer Dordrecht; Kresge, C.T., Leonowicz, M.E., Roth, W.J., Vartuli, J.C., Beck, J.S., Ordered mesoporous molecular sieves synthesized by a liquid-crystal template mechanism (1992) Nature, 359 (6397), pp. 710-712. , DOI 10.1038/359710a0; Beck, J.S., Vartuli, J.C., Roth, W.J., Leonowicz, M.E., Kresge, C.T., Schmitt, K.D., A new family of mesoporous molecular sieves prepared with liquid crystal templates (1992) J Am Chem Soc, 114, pp. 10834-10843. , 1:CAS:528:DyaK38Xms1entr8%3D 10.1021/ja00053a020; Li, Y.Y., Li, J., Nakajima, B., Nanostructured porous biomaterials for controlled drug release systems (2008) Biomaterials-fabrication and Processing, pp. 196-206. , K.C. Paul L. Xuanyong (eds). CRC Press, Taylor & Francis Group New York. 10.1201/9780849379741; Herzberg, G., (1945) The Infrared and Raman Spectra of Poliatomic Molecules, , D van Nostrand Company, Inc. New York; Awonusi, A., Morris, M.D., Tecklenburg, M.M.J., Carbonate assignment and calibration in the Raman spectrum of apatite (2007) Calcified Tissue International, 81 (1), pp. 46-52. , DOI 10.1007/s00223-007-9034-0; Fowler, B.O., Infrared studies of apatites. I. Vibrational assignments for calcium, strontium, and barium hydroxyapatites utilizing isotopic substitution (1974) Inorg Chem, 13, pp. 194-207. , 1:CAS:528:DyaE2cXlsVWktw%3D%3D 10.1021/ic50131a039; Aza, P.N., Santos, C., Pazo, A., Aza, S., Cuscó, R., Artus, L., Vibrational properties of calcium phospate coumpounds. 1. Raman spectrum of β-tricalcium phosphate (1997) Chem Mater, 9, pp. 912-915. , 10.1021/cm960425d
Keywords: Ammonium compounds; Aqueous suspensions; article; Bromine compounds; Calcium; calcium phosphate; cationic surfactant; Cationic surfactants; Cations; Cetrimonium Compounds; Cetyltrimethylammonium bromide; chemical composition; Chemical compositions; Chemical structure; Crystallographic characteristics; Dyes; Heat treatment temperature; High quality; hydroxyapatite; Microscopy, Electron, Scanning; Microscopy, Electron, Transmission; nanorod; Nanorods; Nanotubes; Phosphate compounds; priority journal; Pyrolysis; Scanning electron microscopy; Sintering; Sintering temperatures; Surface-Active Agents; Surfactant template method; Surfactant templating; Suspensions (fluids); synthesis; Synthesis and characterizations; Thermal decompositions; X-Ray Diffraction

Targeted gene delivery into peripheral sensorial neurons mediated by self-assembled vectors composed of poly(ethylene imine) and tetanus toxin fragment c - Oliveira, H.; Fernandez, R.; Pires, L.R.; Martins, M.C.L.; Simões, S.; Barbosa, M.A.; Pêgo, A.P. (Journal of Controlled ReleaseJ. Control. Release, 2010)
A simple, safe and efficient system that can specifically transfect peripheral sensorial neurons can bring new answers to address peripheral neuropathies. A multi-component non-viral gene delivery vector targeted to peripheral nervous system cells was developed, using poly(ethylene imine) (PEI) as starting material. A binary DNA/polymer complex based on thiolated PEI (PEISH) was optimized, considering complex size and zeta potential and the ability to transfect a sensorial neuron cell line (ND7/23). The 50. kDa non-toxic fragment from tetanus toxin (HC), which has been previously shown to interact specifically with peripheral neurons and to undergo retrograde transport, was grafted to the complex core via a bifunctional PEG (HC-PEG) reactive for the thiol moieties present in the complex surface. Several formulations of HC-PEG ternary complexes were tested for targeting, by assessing the extent of cellular internalization and levels of transfection, in both the ND7/23 and NIH 3 T3 (fibroblast) cell lines. Targeted gene transfer to the neuronal cell line was observed for the complex formulations containing 5 and 7.5. Μg of HC-PEG. Finally, our results demonstrate that the developed ternary vectors are able to transfect primary cultures of dorsal root ganglion dissociated neurons in a targeted manner and elicit the expression of a relevant neurotrophic factor. © 2010 Elsevier B.V.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2010.01.018PubMed ID: 20093157Language of Original Document: EnglishCorrespondence Address: Pêgo, A.P.; INEB-Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; macrogol, 25322-68-3; polyethyleneimine, 74913-72-7; DNA, 9007-49-2; Imines; Peptide Fragments; Polyethylenes; Tetanus Toxin; poly(ethylene imine); tetanus toxin fragment CReferences: Rodriguez, F.J., Valero-Cabre, A., Navarro, X., Regeneration and functional recovery following peripheral nerve injury (2004) Drug Discov. Today, 1 (2), pp. 177-185;Sahenk, Z., Neurotrophins and peripheral neuropathies (2006) Brain Pathol., 16 (4), pp. 311-319; Apfel, S.C., Kessler, J.A., Neurotrophic factors in the therapy of peripheral neuropathy (1995) Baillieres Clin. Neurol., 4 (3), pp. 593-606; Apfel, S.C., Is the therapeutic application of neurotrophic factors dead? (2002) Ann. Neurol., 51 (1), pp. 8-11; Glorioso, J.C., Mata, M., Fink, D.J., Therapeutic gene transfer to the nervous system using viral vectors (2003) J. Neurovirol., 9 (2), pp. 165-172; Boussif, O., Lezoualc'h, F., Zanta, M.A., Mergny, M.D., Scherman, D., Demeneix, B., A versatile vector for gene and oligonucleotide transfer into cells in culture and in vivo: polyethylenimine (1995) Proc. Natl. Acad. Sci. U.S.A., 92 (16), pp. 7297-7301; Coll, J.L., Chollet, P., Brambilla, E., Desplanques, D., Behr, J.P., Favrot, M., In vivo delivery to tumors of DNA complexed with linear polyethylenimine (1999) Hum. Gene Ther., 10 (10), pp. 1659-1666; Schaffer, D.V., Lauffenburger, D.A., Optimization of cell surface binding enhances efficiency and specificity of molecular conjugate gene delivery (1998) J. Biol. Chem., 273 (43), pp. 28004-28009; Zanta, M.A., Boussif, O., Adib, A., Behr, J.P., In vitro gene delivery to hepatocytes with galactosylated polyethylenimine (1997) Bioconjug. Chem., 8 (6), pp. 839-844; Diebold, S.S., Lehrmann, H., Kursa, M., Wagner, E., Cotten, M., Zenke, M., Efficient gene delivery into human dendritic cells by adenovirus polyethylenimine and mannose polyethylenimine transfection (1999) Hum. Gene Ther., 10 (5), pp. 775-786; Blessing, T., Kursa, M., Holzhauser, R., Kircheis, R., Wagner, E., Different strategies for formation of PEGylated EGF-conjugated PEI/DNA complexes for targeted gene delivery (2001) Bioconjug. Chem., 12 (4), pp. 529-537; Erbacher, P., Remy, J.S., Behr, J.P., Gene transfer with synthetic virus-like particles via the integrin-mediated endocytosis pathway (1999) Gene Ther., 6 (1), pp. 138-145; Kircheis, R., Kichler, A., Wallner, G., Kursa, M., Ogris, M., Felzmann, T., Coupling of cell-binding ligands to polyethylenimine for targeted gene delivery (1997) Gene Ther., 4 (5), pp. 409-418; Park, I.K., Lasiene, J., Chou, S.H., Horner, P.J., Pun, S.H., Neuron-specific delivery of nucleic acids mediated by Tet1-modified poly(ethylenimine) (2007) J. Gene Med., 9 (8), pp. 691-702; Kwon, E.J., Bergen, J.M., Park, I.K., Pun, S.H., Peptide-modified vectors for nucleic acid delivery to neurons (2008) J. Control. Release, 132 (3), pp. 230-235; Price, D.L., Griffin, J., Young, A., Peck, K., Stocks, A., Tetanus toxin: direct evidence for retrograde intraaxonal transport (1975) Science, 188 (4191), pp. 945-947; Figueiredo, D.M., Hallewell, R.A., Chen, L.L., Fairweather, N.F., Dougan, G., Savitt, J.M., Delivery of recombinant tetanus-superoxide dismutase proteins to central nervous system neurons by retrograde axonal transport (1997) Exp. Neurol., 145 (2 PART 1), pp. 546-554; Fishman, P.S., Savitt, J.M., Farrand, D.A., Enhanced CNS uptake of systemically administered proteins through conjugation with tetanus C-fragment (1990) J. Neurol. Sci., 98 (2-3), pp. 311-325; Coen, L., Osta, R., Maury, M., Brulet, P., Construction of hybrid proteins that migrate retrogradely and transynaptically into the central nervous system (1997) Proc. Natl. Acad. Sci. U.S.A., 94 (17), pp. 9400-9405; Knight, A., Carvajal, J., Schneider, H., Coutelle, C., Chamberlain, S., Fairweather, N., Non-viral neuronal gene delivery mediated by the HC fragment of tetanus toxin (1999) Eur. J. Biochem., 259 (3), pp. 762-769; Carlisle, R.C., Etrych, T., Briggs, S.S., Preece, J.A., Ulbrich, K., Seymour, L.W., Polymer-coated polyethylenimine/DNA complexes designed for triggered activation by intracellular reduction (2004) J. Gene Med., 6 (3), pp. 337-344; Goula, D., Remy, J.S., Erbacher, P., Wasowicz, M., Levi, G., Abdallah, B., Size, diffusibility and transfection performance of linear PEI/DNA complexes in the mouse central nervous system (1998) Gene Ther., 5 (5), pp. 712-717; Sinha, K., Box, M., Lalli, G., Schiavo, G., Schneider, H., Groves, M., Analysis of mutants of tetanus toxin Hc fragment: ganglioside binding, cell binding and retrograde axonal transport properties (2000) Mol. Microbiol., 37 (5), pp. 1041-1051; Ellman, G.L., Tissue sulfhydryl groups (1959) Arch. Biochem. Biophys., 82 (1), pp. 70-77; (1993) Iodine-125, a Guide to Radioionation Techniques, , Amersham Life Science; O'brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar Blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) Eur. J. Biochem., 267 (17), pp. 5421-5426; Pollard, H., Remy, J.S., Loussouarn, G., Demolombe, S., Behr, J.P., Escande, D., Polyethylenimine but not cationic lipids promotes transgene delivery to the nucleus in mammalian cells (1998) J. Biol. Chem., 273 (13), pp. 7507-7511; Neu, M., Fischer, D., Kissel, T., Recent advances in rational gene transfer vector design based on poly(ethylene imine) and its derivatives (2005) J. Gene Med., 7 (8), pp. 992-1009; Moffatt, S., Papasakelariou, C., Wiehle, S., Cristiano, R., Successful in vivo tumor targeting of prostate-specific membrane antigen with a highly efficient J591/PEI/DNA molecular conjugate (2006) Gene Ther., 13 (9), pp. 761-772; Kircheis, R., Ostermann, E., Wolschek, M.F., Lichtenberger, C., Magin-Lachmann, C., Wightman, L., Tumor-targeted gene delivery of tumor necrosis factor-alpha induces tumor necrosis and tumor regression without systemic toxicity (2002) Cancer Gene Ther., 9 (8), pp. 673-680; Bellomo, G., Vairetti, M., Stivala, L., Mirabelli, F., Richelmi, P., Orrenius, S., Demonstration of nuclear compartmentalization of glutathione in hepatocytes (1992) Proc. Natl. Acad. Sci. U.S.A., 89 (10), pp. 4412-4416; Liu, H.S., Jan, M.S., Chou, C.K., Chen, P.H., Ke, N.J., Is green fluorescent protein toxic to the living cells? (1999) Biochem. Biophys. Res. Commun., 260 (3), pp. 712-717; Baens, M., Noels, H., Broeckx, V., Hagens, S., Fevery, S., Billiau, A.D., The dark side of EGFP: defective polyubiquitination (2006) PLoS One, 1, pp. e54; Taghizadeh, R.R., Sherley, J.L., CFP and YFP, but not GFP, provide stable fluorescent marking of rat hepatic adult stem cells (2008) J. Biomed. Biotechnol., 2008. , 453590; Liu, J.K., Tenga, Q.S., Garrity-Moses, M., Federici, T., Tanase, D., Imperiale, M.J., A novel peptide defined through phage display for therapeutic protein and vector neuronal targeting (2005) Neurobiol. Dis., 19 (3), pp. 407-418; Fishman, P.S., Carrigan, D.R., Retrograde transneuronal transfer of the C-fragment of tetanus toxin (1987) Brain Res., 406 (1-2), pp. 275-279
Keywords: Aberrations; animal cell; Animals; article; Bifunctional; Cell culture; Cell Line, Tumor; Cell lines; cell strain 3T3; Cells, Cultured; Cellular internalization; Chemical modification; Complex cores; Complex formulations; Complex surface; controlled study; DNA; DNA protein complex; Dorsal root ganglia; Efficient systems; embryo; Ethylene; Female; Gene transfer; genetic transfection; Imines; internalization; macrogol; Mice; mouse; Multicomponents; nanoparticle; nanoparticles; neuroblastoma cell; Neuronal cell; Neurons; neurotrophic factor; Neurotrophic factors; NIH 3T3 Cells; Nitrogen compounds; Non-viral; Non-viral gene delivery; nonhuman; Nonviral; nonviral gene delivery system; Nucleic acids; Particle Size; Peptide Fragments; Peripheral nervous system; Peripheral neuropathy; Plasmids; Polyethylene Glycols; Polyethylene oxides; Polyethyleneimine; Polyethylenes; Primary culture; priority journal; process optimization; protein expression; rat; Rats; Rats, Wistar; Regenerative Medicine; Self-assembled; sensory nerve cell; spinal ganglion; Starting materials; Targeted; Targeted gene delivery; Ternary complex; Ternary vectors; Tetanus toxin; tetanus toxin fragment c; Transfection; unclassified drug; Zeta potential

TNF-α regulates the effects of irradiation in the mouse bone marrow microenvironment - Cachaço, A.S.; Carvalho, T.; Santos, A.C.; Igreja, C.; Fragoso, R.; Rio, C.O.; Ferreira, M.; Serpa, J.; Correia, S.; Pinto-Do-Ó, P.; Dias, S. (PLoS ONEPLoS ONE, 2010)
Background: Secondary bone marrow (BM) myelodysplastic syndromes (MDS) are increasingly common, as a result of radio or chemotherapy administered to a majority of cancer patients. Patients with secondary MDS have increased BM cell apoptosis, which results in BM dysfunction (cytopenias), and an increased risk of developing fatal acute leukemias. In the present study we asked whether TNF-α, known to regulate cell apoptosis, could modulate the onset of secondary MDS. Principal Findings:We show that TNF-α is induced by irradiation and regulates BM cells apoptosis in vitro and in vivo. In contrast to irradiated wild type (WT) mice, TNF-α deficient (TNF-α KO) mice or WT mice treated with a TNF-α-neutralizing antibody were partially protected from the apoptotic effects of irradiation. Next we established a 3-cycle irradiation protocol, in which mice were sub-lethally irradiated once monthly over a 3 month period. In this model, irradiated WT mice presented loss of microsatellite markers on BM cells, low white blood cell (WBC) counts, reduced megakaryocyte (MK) and platelet levels (thrombocytopenia) and macrocytic anemia, phenoypes that suggest the irradiation protocol resulted in BM dysfunction with clinical features of MDS. In contrast, TNF-α KO mice were protected from the irradiation effects: BM cell apoptosis following irradiation was significantly reduced, concomitant with sustained BM MK numbers and absence of other cytopenias. Moreover, irradiated WT mice with long term (≥5 months) BM dysfunction had increased BM angiogenesis, MMPs and VEGF and NFkB p65, suggestive of disease progression. Conclusion:Taken together, our data shows that TNF-α induction following irradiation modulates BM cell apoptosis and is a crucial event in BM dysfunction, secondary MDS onset and progression. © 2010 Cachaço et al.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusArt. No.: e8980doi: 10.1371/journal.pone.0008980Language of Original Document: EnglishCorrespondence Address: Cachaço, A. S.; Angiogenesis Laboratory, Centro de Investigação em Patobiologia Molecular (CIPM), Instituto Portugues de Oncologia de Francisco Gentil, Lisboa, PortugalChemicals/CAS: vasculotropin, 127464-60-2; vasculotropin A, 489395-96-2; Antibodies, Neutralizing; Matrix Metalloproteinases, 3.4.24.-; Tumor Necrosis Factor-alpha; Vascular Endothelial Growth Factor AReferences: Baud, V., Karin, M., Signal transduction by tumor necrosis factor and its relatives (2001) Trends Cell Biol, 11, pp. 372-377;Balkwill, F., Mantovani, A., Inflammation and cancer: Back to Virchow? (2001) Lancet, 357, pp. 539-345; Lejeune, F.J., Rüegg, C., Recombinant human tumor necrosis factor: An efficient agent for cancer treatment (2006) Bull Cancer, 93 (8), pp. E90-100; Moore, R.J., Owens, D.M., Stamp, G., Arnott, C., Burke, F., Mice deficient in tumor necrosis factor-alpha are resistant to skin carcinogenesis (1999) Nat Med, 5, pp. 828-831; Scott, K.A., Arnott, C.H., Robinson, S.C., Moore, R.J., Thompson, R.G., TNF-alpha regulates epithelial expression of MMP-9 and integrin alphavbeta6 during tumour promotion. A role for TNF-alpha in keratocyte migration? (2004) Oncogene, 23, pp. 6954-6966; Hagemann, T., Robinson, S.C., Schulz, M., Trumper, L., Balkwill, F.R., Enhanced invasiveness of breast cancer cell lines upon co-cultivation with macrophages is due to TNF-alpha dependent up-regulation of matrix metalloproteases (2004) Carcinogenesis, 25 (8), pp. 1543-1549; Yang, W.L., Godwin, A.K., Xu, X.X., Tumor necrosis factor-alpha-induced matrix proteolytic enzyme production and basement membrane remodeling by human ovarian surface epithelial cells: Molecular basis linking ovulation and cancer risk (2004) Cancer Res, 64 (4), pp. 1534-1540; Redondo-Muñoz, J., Escobar-Díaz, E., Samaniego, R., Terol, M.J., García-Marco, J.A., MMP-9 in B-cell chronic lymphocytic leukemia is up-regulated by alpha4beta1 integrin or CXCR4 engagement via distinct signaling pathways, localizes to podosomes, and is involved in cell invasion and migration (2006) Blood, 108 (9), pp. 3143-3151; Rosselli, F., Sancean, J., Gluckman, E., Abnormal lymphokine production: A novel feature of the genetic disease Fanconi anemia. In vitro and in vivo spontaneous overproduction of tumor necrosis factor α (1994) Blood, 83 (5), pp. 1216-1225; Dufour, C., Corcione, A., Svahn, J., Haupt, R., Poggi, V., TNF-alpha and IFN-gamma are overexpressed in the bone marrow of Fanconi anemia patients and TNF-alpha suppresses erythropoiesis in vitro (2003) Blood, 102 (6), pp. 2053-2059; Kuruvilla J, Leitch HA, Vickars LM, Galbraith PF, Li CH, et al. (2003) Aplastic anemia following administration of a tumor necrosis factor-alpha inhibitor. Eur J Haematol 71(5): 396-8. Erratum in: Eur J Haematol. (2004) 72(4):306Hara, T., Ando, K., Tsurumi, H., Moriwaki, H., Excessive production of tumor necrosis factor-alpha by bone marrow T lymphocytes is essential in causing bone marrow failure in patients with aplastic anemia (2004) Eur J Haematol, 73 (1), pp. 10-16; Kerbauy, D.B., Deeg, H.J., Apoptosis and antiapoptotic mechanisms in the progression of myelodysplastic syndromes (2007) Exp Hematol, 35 (11), pp. 1739-1746; Lv, L., Kerzic, P., Lin, G., Schnatter, A.R., Bao, L., The TNF-alpha 238A polymorphism is associated with susceptibility to persistent bone marrow dysplasia following chronic exposure to benzene (2007) Leuk Res, 31 (11), pp. 1479-1485; Boula, A., Voulgarelis, M., Giannouli, S., Katrinakis, G., Psyllaki, M., Effect of cA2 anti.tumor necrosis factor-alpha antibody therapy on hematopoiesis of patients with myelodysplastic syndromes (2006) Clin Cancer Res, 12, pp. 3099-3108; Deeg, H.J., Gotlib, J., Beckham, C., Dugan, K., Holmberg, L., Soluble TNF receptor fusion protein (etanercept) for the treatment of myelodysplastic syndrome: A pilot study (2002) Leukemia, 16 (2), pp. 162-164; Maciejewski JP, Risitano AM, Sloand EM, Wisch L, Geller N, et al. (2002) Br J Haematol 117(1): 119-26. Erratum in: Br J Haematol (2002) 117(4):1002. Ristiano Antonio M [corrected to Risitano Antonio M]De Roos, A.J., Deeg, H.J., Davis, S., A population-based study of survival in patients with secondary myelodysplastic syndromes (MDS): Impact of type and treatment of primary cancers (2007) Cancer Causes Control, 18 (10), pp. 1199-1208; Malcovati, L., Nimer, S.D., Myelodysplastic syndromes: Diagnosis and Staging (2008) Cancer Control, 15 (4 SUPPL.EMENT), pp. 4-13; Haran-Ghera, N., Peled, A., Krautghamer, R., Resnitzky, P., Initiation and promotion in radiation-induced myeloid leukemia (1992) Leukemia, 6 (7), pp. 689-695; Padmanabhan, A., Baker, J.A., Zirpoli, G., Sait, S.N., Ford, L.A., Acute myeloid leukemia and myelodysplastic syndrome following breast cancer: Increased frequency of other cancers and of cancers in multiple family members (2008) Leuk Res, 32 (12), pp. 1820-1823; Zhang, Y., Harada, A., Bluethmann, H., Wang, J.B., Nakao, S., Tumor necrosis factor (TNF) is a physiologic regulator of hematopoietic progenitor cells: Increase of early hematopoietic progenitor cells in TNF receptor p55-deficient mice in vivo and potent inhibition of progenitor cell proliferation by TNF alpha in vitro (1995) Blood, 86 (8), pp. 2930-2937; Rebel, V.I., Hartnett, S., Hill, G.R., Lazo-Kallanian, S.B., Ferrara, J.L., Essential role for the p55 tumor necrosis factor receptor in regulating hematopoiesis at a stem cell level (1999) J Exp Med, 190 (10), pp. 1493-1504; Drutskaya, M.S., Ortiz, M., Liepinsh, D.J., Kuprash, D.V., Nedospasov, S.A., Inhibitory effects of tumor necrosis factor on hematopoiesis seen in vitro are translated to increased numbers of both committed and multipotent progenitors in TNF-deficient mice (2005) Exp Hematol, 33 (11), pp. 1348-1356; Rübe, C.E., Wilfert, F., Uthe, D., Schmid, K.W., Knoop, R., Modulation of radiation-induced tumour necrosis factor alpha (TNF-alpha) expression in the lung tissue by pentoxifylline (2002) Radiother Oncol, 64 (2), pp. 177-187; Zhang, M., Qian, J., Xing, X., Kong, F.M., Zhao, L., Inhibition of the tumor necrosis factor-alpha pathway is radioprotective for the lung (2008) Clin Cancer Res, 14 (6), pp. 1868-1876; Daigle, J.L., Hong, J.H., Chiang, C.S., McBride, W.H., The role of tumor necrosis factor signaling pathways in the response of murine brain to irradiation (2001) Cancer Res, 61 (24), pp. 8859-8865; Dy, L.C., Pei, Y., Travers, J.B., Augmentation of ultraviolet B radiation-induced tumor necrosis factor production by the epidermal platelet-activating factor receptor (1999) J Biol Chem, 274 (38), pp. 26917-26921; Müller, K., Meineke, V., Radiation-induced alterations in cytokine production by skin cells (2007) Exp Hematol, 35 (4 SUPPL. 1), pp. 96-104; Tolle, D.V., Seed, T.M., Fritz, T.E., Lombard, L.S., Poole, C.M., Acute monocytic leukemia in an irradiated Beagle (1979) Vet Pathol, 16 (2), pp. 243-254; Seed, T.M., Chubb, G.T., Tolle, D.V., Sequential changes in bone marrow architecture during continuous low dose gamma irradiation (1981) Scan Electron Microsc, 4, pp. 61-72; Sato, H., Seiki, M., Regulatory mechanism of 92 kDa type IV collagenase gene expression which is associated with invasiveness of tumor cells (1993) Oncogene, 8, pp. 395-405; Wielockx, B., Lannoy, K., Shapiro, S.D., Inhibition of matrix metalloproteinases blocks lethal hepatitis and apoptosis induced by tumor necrosis factor and allows safe antitumor therapy (2001) Nat Med, 7, pp. 1202-1208; Heissig B, Hattori K, Dias S, Friedrich M, Ferris B, et al. (2002) Recruitment of stem and progenitor cells from the bone marrow niche requires MMP-9 mediated release of kit-ligand. Cell 31:109(5): 625-37.35Natoli G, Costanzo A, Guido F, Moretti F, Bernardo A, et al. (1998) Nuclear factor kB-independent cytoprotective pathways originating at tumor necrosis factor receptor-associated factor 2. J Biol Chem 273(47): 31262-72.36Barkett, M., Gilmore, T.D., Control of apoptosis by Rel/NF-kappaB transcription factors (1999) Oncogene, 18 (49), pp. 6910-6924; Priestley, G.V., Scott, L.M., Ulyanova, T., Papayannopoulou, T., Lack of a4 integrin expression in stem cells restricts competitive function and self-renewal activity (2006) Blood, 107, pp. 2959-2967; Walkley, C.R., Shea, J.M., Sims, N.A., Purton, L.E., Orkin, S.H., Rb regulates interactions between hematopoietic stem cells and their bone marrow microenvironment (2007) Cell, 129 (6), pp. 1081-1095. , A; Walkley, C.R., Olsen, G.H., Dworkin, S., Fabb, S.A., Swann, J., A microenvironment-induced myeloproliferative syndrome caused by retinoic acid receptor gamma deficiency (2007) Cell, 129 (6), pp. 1097-1110. , B; Leone, G., Pagano, L., Ben-Yehuda, D., Voso, M.T., Therapy-related leukemia and myelodysplasia: Susceptibility and incidence (2007) Haematologica, 92 (10), pp. 1389-1398; Reza, S., Shetty, V., Dar, S., Qawi, H., Raza, A., Tumor necrosis factor-α levels decrease with anticytokine therapy in patients with myelodysplastic syndromes (1998) J Interferon Cytokine Res, 18 (10), pp. 871-877; Raza, A., Qawi, H., Lisak, L., Andric, T., Dar, S., Patients with myelodysplastic syndromes benefit from palliative therapy with amifostine, pentoxifylline, and ciprofloxacin with or without dexamethasone (2000) Blood, 95 (5), pp. 1580-1587
Keywords: angiogenesis; animal; animal cell; animal experiment; animal model; animal tissue; Animals; Antibodies, Neutralizing; apoptosis; article; Blood; blood cell count; Blotting, Western; bone marrow; bone marrow cell; Bone Marrow Cells; C57BL mouse; Cell Line; clinical feature; controlled study; cytokine production; disease course; drug effect; Enzyme Activation; flow cytometry; genetics; immunology; in vitro study; in vivo study; irradiation; leukocyte; leukocyte count; Leukocytes; macrocytic anemia; male; matrix metalloproteinase; Matrix Metalloproteinases; megakaryocyte; Megakaryocytes; metabolism; Mice; Mice, Inbred C57BL; Mice, Knockout; microenvironment; microsatellite marker; mouse; mouse mutant; Mus; myelodysplastic syndrome; neovascularization (pathology); Neovascularization, Pathologic; neutralizing antibody; nonhuman; Pathology; phenotype; protein expression; radiation dose; radiation exposure; Reverse Transcriptase Polymerase Chain Reaction; reverse transcription polymerase chain reaction; thrombocytopenia; transcription factor RelA; tumor necrosis factor alpha; tumor necrosis factor alpha antibody; Tumor Necrosis Factor-alpha; Vascular Endothelial Growth Factor A; vascularization; vasculotropin; vasculotropin A; Western blotting; zymography

Automated Arabidopsis plant root cell segmentation based on SVM classification and region merging - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Maria Mendonça, A.; Campilho, A. (Computers in Biology and MedicineComput. Biol. Med., 2009)
To obtain development information of individual plant cells, it is necessary to perform in vivo imaging of the specimen under study, through time-lapse confocal microscopy. Automation of cell detection/marking process is important to provide research tools in order to ease the search for special events, such as cell division. In this paper we discuss an automatic cell detection approach for Arabidopsis thaliana based on segmentation, which selects the best cell candidates from a starting watershed-based image segmentation and improves the result by merging adjacent regions. The selection of individual cells is obtained using a support vector machine (SVM) classifier, based on a cell descriptor constructed from the shape and edge strength of the cells' contour. In addition we proposed a novel cell merging criterion based on edge strength along the line that connects adjacent cells' centroids, which is a valuable tool in the reduction of cell over-segmentation. The result is largely pruned of badly segmented and over-segmented cells, thus facilitating the study of cells. When comparing the results after merging with the basic watershed segmentation, we obtain 1.5% better coverage (increase in F-measure) and up to 27% better precision in correct cell segmentation. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: CBMDAdoi: 10.1016/j.compbiomed.2009.06.008PubMed ID: 19604506Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Portugal; email: marcuzzo@fe.up.ptReferences: Baeza-Yates, R., Ribeiro-Neto, B., (1999) Modern Information Retrieval, , ACM Press;Bleau, A., Leon, L., Watershed-based segmentation and region merging (2000) Computer Vision and Image Understanding, 77 (3), pp. 317-370; M. Brown, W. Grundy, L.D.N. Cristianini, C. Sugnet, T. Furey, M. Ares, D. Haussler, Knowledge-based analysis of microarray gene expression data using support vector machines, in: Proceedings of the National Academy of Sciences, 97 (1), 1999, pp. 262-267Burges, C., A tutorial on support vector machines for pattern recognition (1998) Data Mining and Knowledge Discovery, 2 (2), pp. 121-167; Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem (2006) Plant Journal, 48, pp. 619-627; Chang, C., Lin, C., (2001) Libsvm: A library for support vector machines, , http://www.csie.ntu.edu.tw/∼cjlin/libsvm/faq.html#f203, Software available online at; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation classification, and tracking of cancer cell nuclei in time-lapse microscopy (2006) IEEE Transactions on Biomedical Engineering, 53 (4), pp. 762-766; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Transactions on Image Processing, 16 (8), pp. 2080-2095; (2004) Kernel Methods in Computational Biology, Computational Molecular Biology, , B. Schölkopf, K. Tsuda, J.-P. Vert, Eds, MIT Press, Cambridge, MA; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of Arabidopsis thaliana root meristem in confocal microscopy (2004) Springer Lecture Notes in Computer Science, 3212, pp. 166-174. , Proceedings of the International Conference on Image Analysis and Recognition, Springer, Berlin; Grandjean, O., Vernoux, T., Laufs, P., Belcram, K., Mizukami, Y., Traas, J., In vivo analysis of cell division, cell growth, and differentiation at the shoot apical meristem in Arabidopsis (2004) Plant Cell, 16 (1), pp. 74-87; Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in Arabidopsis thaliana provided by a simple mathematical model (2006) Journal of Plant Research, 119, pp. 85-93; Kittler, J., Hatef, M., Duin, R.P.W., Matas, J., On combining classifiers (1998) IEEE Transactions on Pattern Analysis and Machine Intelligence, 20 (3), pp. 226-239; P. Kovesi, Symmetry and asymmetry from local phase, in: Proceedings of the 10th Australian Joint Conference on Artificial Intelligence, December 1997, pp. 185-190P. Kovesi, Edges are not just steps, in: Proceedings of the Fifth Asian Conference on Computer Vision, January 2002, pp. 822-827Liao, L., Noble, W.S., Combining pairwise sequence similarity and support vector machines for remote protein homology detection (2002) Proceedings of the Sixth Annual International Conference on Computational Molecular Biology, pp. 225-232. , ACM Press; Luc, V., Soille, P., Watersheds in digital spaces: an efficient algorithm based on immersion simulations (1991) IEEE Transactions on Pattern Analysis and Machine Intelligence, 13 (6), pp. 583-598; Mao, K., Zhao, P., Tan, P.-H., Supervised learning-based cell image segmentation for p53 immunohistochemistry (2006) IEEE Transactions on Biomedical Engineering, 53 (6), pp. 1153-1163; M. Marcuzzo, P. Quelhas, A. Campilho, A.M. Mendonça, A.C. Campilho, Automatic cell segmentation from confocal microscopy images of the Arabidopsis root, in: IEEE International Symposium on Biomedical Imaging, May 2008, pp. 712-715Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A.C., A hybrid approach for cell image segmentation (2008) Springer Lecture Notes in Computer Science, 5112, pp. 739-749. , Proceedings of the International Conference on Image Analysis and Recognition, Springer, Berlin; Meyer, F., Beucher, S., Morphological segmentation (1990) Journal of Visual Communication and Image Representation, 1 (1), pp. 21-46; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Transactions on Pattern Analysis and Machine Intelligence, 7 (12), pp. 629-639; T. Roberts, S. Mckenna, N. Wuyts, T. Valentine, A. Bengough, Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo, in: IEEE Workshop on Motion & Video Computing, February 2007, pp. 13-21Sathiya Keerthi, S., Lin, C.-J., Asymptotic behaviors of support vector machines with Gaussian kernel (2003) Neural Computation, 15 (7), pp. 1667-1689; Vapnik, V., (1998) Statistical Learning Theory, , Wiley, New York
Keywords: accuracy; Arabidopsis; Arabidopsis plant; Arabidopsis thaliana; article; artificial intelligence; automation; Bioinformatics; Biological cells; Biomedical image processing; Cell detection; Cell divisions; Cell membranes; Cell merging; cell proliferation; Cell segmentation; Cell Shape; Cell Wall; Computer simulation; confocal microscopy; controlled study; Descriptor; F-measure; Image analysis; image processing; Image Processing, Computer-Assisted; Image segmentation; Imaging systems; In-Vivo imaging; Individual cells; Landforms; Merging; Models, Biological; nonhuman; Over segmentation; Plant cells; plant root; Plant roots; Plants (botany); priority journal; Region-merging; Research tools; root morphology; Segmented cell; signal noise ratio; support vector machine; Support vector machines; SVM classification; Watershed segmentation; Watersheds

Cancer cell angiogenic capability is regulated by 3D culture and integrin engagement - Fischbach, C.; Hyun, J.K.; Hsiong, S.X.; Evangelista, M.B.; Yuen, W.; Mooney, D.J. (Proceedings of the National Academy of Sciences of the United States of AmericaProc. Natl. Acad. Sci. U. S. A., 2009)
Three-dimensional culture alters cancer cell signaling; however, the underlying mechanisms and importance of these changes on tumor vascularization remain unclear. A hydrogel system was used to examine the role of the transition from 2D to 3D culture, with and without integrin engagement, on cancer cell angiogenic capability. Three-dimensional culture recreated tumor microenvironmental cues and led to enhanced interleukin 8 (IL-8) secretion that depended on integrin engagement with adhesion peptides coupled to the polymer. In contrast, vascular endothelial growth factor (VEGF) secretion was unaffected by 3D culture with or without substrate adhesion. IL-8 diffused greater distances and was present in higher concentrations in the systemic circulation, relative to VEGF. Implantation of a polymeric IL-8 delivery system into GFP bone marrow-transplanted mice revealed that localized IL-8 up-regulation was critical to both the local and systemic control of tumor vascularization in vivo. In summary, 3D integrin engagement within tumor microenvironments regulates cancer cell angiogenic signaling, and controlled local and systemic blockade of both IL-8 and VEGF signaling may improve antiangiogenic therapies. © 2009 by The National Academy of Sciences of the USA.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: PNASAdoi: 10.1073/pnas.0808932106PubMed ID: 19126683Language of Original Document: EnglishCorrespondence Address: Mooney, D. J.; School of Engineering and Applied Sciences, Harvard University, 40 Oxford Street, Cambridge, MA 02138, United States; email: mooneyd@seas.harvard.eduChemicals/CAS: arginylglycylaspartic acid, 99896-85-2; interleukin 8, 114308-91-7; vasculotropin, 127464-60-2; Hydrogels; Integrins; Interleukin-8; Vascular Endothelial Growth Factor AReferences: Debnath, J., Brugge, J.S., Modelling glandular epithelial cancers in 3-dimensional cultures (2005) Nat Rev Cancer, 5, pp. 675-688;Wang, F., Reciprocal interactions between β1-integrin and epidermal growth factor receptor in 3-dimensional basement membrane breast cultures: A different perspective in epithelial biology (1998) Proc Natl Acad Sci USA, 95, pp. 14821-14826; Fischbach, C., Engineering tumors with 3D scaffolds (2007) Nat Methods, 4, pp. 855-860; Paszek, M.J., Tensional homeostasis and the malignant phenotype (2005) Cancer Cell, 8, pp. 241-254; Hanahan, D., Weinberg, R.A., The hallmarks of cancer (2000) Cell, 100, pp. 57-70; De, S., VEGF-integrin interplay controls tumor growth and vascularization (2005) Proc Natl Acad Sci USA, 102, pp. 7589-7594; Lowrie, A.G., Salter, D.M., Ross, J.A., Latent effects of fibronectin, α5β1 integrin, αvβ5 integrin, and the cytoskeleton regulate pancreatic carcinoma cell IL-8 secretion (2004) Br J Cancer, 91, pp. 1327-1334; Cukierman, E., Pankov, R., Stevens, D.R., Yamada, K.M., Taking cell matrix adhesions to the third dimension (2001) Science, 294, pp. 1708-1712; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Lingen, M.W., Angiogenesis in the development of head and neck cancer and its inhibition by chemopreventive agents (1999) Crit Rev Oral Biol Med, 10, pp. 153-164; Fischbach, C., Mooney, D., Polymeric systems for bioinspired delivery of angiogenic molecules (2006) Adv Polym Sci, 203, pp. 191-221; Ruoslahti, E., Pierschbacher, M.D., New perspectives in cell adhesion: RGD and integrins (1987) Science, 238, pp. 491-497; Kong, H.J., Boontheekul, T., Mooney, D.J., Quantifying the relation between adhesion ligand-receptor bond formation and cell phenotype (2006) Proc Natl Acad Sci USA, 103, pp. 18534-18539; Harris, A.L., Hypoxia: A key regulatory factor in tumour growth (2002) Nat Rev Cancer, 2, pp. 38-47; Xu, L., Hypoxia-induced elevation in interleukin-8 expression by human ovarian carcinoma cells (1999) Cancer Res, 59, pp. 5822-5829; Weaver, V.M., Reversion of the malignant phenotype of human breast cells in three-dimensional cultureandin vivo by integrin-blocking antibodies (1997) J Cell Biol, 137, pp. 231-245; Chung, J., Hypoxia-induced vascular endothelial growth factor transcription and protection from apoptosis are dependent on α6β1 integrin in breast carcinoma cells (2004) Cancer Res, 64, pp. 4711-4716; Ghosh, S., Three-dimensional culture of melanoma cells profoundly affects gene expression profile: A high density oligonucleotide array study (2005) J Cell Physiol, 204, pp. 522-531; De Larco, J.E., A potential role for interleukin-8 in the metastatic phenotype of breast carcinoma cells (2001) Am J Pathol, 158, pp. 639-646; Nemeth, Z.H., Disruption of the actin cytoskeleton results in nuclear factor-κB activation and inflammatory mediator production in cultured human intestinal epithelial cells (2004) J Cell Physiol, 200, pp. 71-81; Xie, K., Interleukin-8 and human cancer biology (2001) Cytokine Growth Factor Rev, 12, pp. 375-391; Casanovas, O., Hicklin, D.J., Bergers, G., Hanahan, D., Drug resistance by evasion of antiangiogenic targeting of VEGF signaling in late-stage pancreatic islet tumors (2005) Cancer Cell, 8, pp. 299-309; Mizukami, Y., Induction of interleukin-8 preserves the angiogenic response in HIF-1α-deficient colon cancer cells (2005) Nat Med, 11, pp. 992-997; Esposito, I., Inflammatory cells contribute to the generation of an angiogenic phenotype in pancreatic ductal adenocarcinoma (2004) J Clin Pathol, 57, pp. 630-636; Ferrara, N., Henzel, W.J., Pituitary follicular cells secrete a novel heparin-binding growth factor specific for vascular endothelial cells (1989) Biochem Biophys Res Commun, 161, pp. 851-858; Gaertner, H.F., Offord, R.E., Site-specific attachment of functionalized poly(ethylene glycol) to the amino terminus of proteins (1996) Bioconjug Chem, 7, pp. 38-44; Goerges, A.L., Nugent, M.A., Regulation of vascular endothelial growth factor binding and activity by extracellular pH (2003) J Biol Chem, 278, pp. 19518-19525; Kuschert, G.S., Identification of a glycosaminoglycan binding surface on human interleukin-8 (1998) Biochemistry, 37, pp. 11193-11201; Kerbel, R., Folkman, J., Clinical translation of angiogenesis inhibitors (2002) Nat Rev Cancer, 2, pp. 727-739; Fischbach, C., Mooney, D.J., Polymers for pro- and antiangiogenic therapy (2007) Biomaterials, 28, pp. 2069-2076; Alsberg, E., Engineering growing tissues (2002) Proc Natl Acad Sci USA, 99, pp. 12025-12030; Simmons, C.A., Dual growth factor delivery and controlled scaffold degradation enhance in vivo bone formation by transplanted bone marrow stromal cells (2004) Bone, 35, pp. 562-569; Comisar, W.A., Kazmers, N.H., Mooney, D.J., Linderman, J.J., Engineering RGD nanopatterned hydrogels to control preosteoblast behavior: A combined computational and experimental approach (2007) Biomaterials, 28, pp. 4409-4417; Alsberg, E., Regulating bone formation via controlled scaffold degradation (2003) J Dent Res, 82, pp. 903-908; Richardson, T.P., Peters, M.C., Ennett, A.B., Mooney, D.J., Polymeric system for dual growth factor delivery (2001) Nat Biotechnol, 19, pp. 1029-1034
Keywords: animal experiment; animal model; Animals; arginylglycylaspartic acid; article; bone marrow transplantation; cancer cell; cancer cell culture; Cell Culture Techniques; concentration (parameters); controlled study; cytokine release; Diffusion; Drug delivery; ECM; Humans; hydrogel; Hydrogels; IL-8; implantation; in vivo study; integrin; Integrins; interleukin 8; Interleukin-8; Mice; microenvironment; Models, Biological; mouse; Mus; Neoplasms; Neovascularization, Pathologic; nonhuman; polymer; priority journal; signal transduction; systemic circulation; Tumor vascularization; upregulation; Vascular Endothelial Growth Factor A; vasculotropin

Cancer invasion and metastasis: Interacting ecosystems - Mareel, M.; Oliveira, M.J.; Madani, I. (Virchows ArchivVirchows Arch., 2009)
Malignant tumors invade and metastasize. They consist of cancer cells, evolving through genetic and epigenetic modulation, mixed with tumor-associated host cells, emerging from resident or bone marrow-derived precursors. These cells establish ecosystems to activate cellular programs for local invasion and distant metastasis. Characteristic of such malignancy-related activities is communication inside ecosystems between cells, ligands, receptor protein complexes, and signaling pathways as well as between ecosystems comprising the primary tumor, lymph node and distant metastasis, bone marrow and blood and lymph circulation. Complexity is another characteristic, resulting from: heterogeneity of the cell populations; the numbers of promoter and suppressor genes, their levels of regulation, and the pleiotropic activities of their products; biological redundancy of the molecular mechanisms underpinning invasion-related activities. Clinical attention is paid to putative new targets, namely host cells, individual molecules and their signaling pathways, as well as the effects of current treatment on invasion and metastasis. © 2009 Springer-Verlag.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: VARCEdoi: 10.1007/s00428-009-0784-0PubMed ID: 19471961Language of Original Document: EnglishCorrespondence Address: Madani, I.; Department of Radiotherapy, Ghent University Hospital, De Pintelaan 185, 9000 Ghent, Belgium; email: indira.madani@ugent.beReferences: Tarin, D., New insights into the pathogenesis of breast cancer metastasis (2006) Breast Disease, 26 (1), pp. 13-25;Stafford, L.J., Vaidya, K.S., Welch, D.R., Metastasis suppressors genes in cancer (2008) Int J Biochem Cell Biol, 40, pp. 874-891; Oliveira, M.J., (2004) The Effect of Bacteria on Colon Cancer Cell Invasion: Molecular Mechanisms Associated, , Faculty of Medicine and Health Sciences. Ghent University. PhD thesis; Madani, I., De Neve, W., Mareel, M., Does ionizing radiation stimulate cancer invasion and metastasis? (2008) Bull Cancer, 95, pp. 292-300; De Wever, O., Mareel, M., Role of tissue stroma in cancer cell invasion (2003) Journal of Pathology, 200 (4), pp. 429-447. , DOI 10.1002/path.1398; Bracke, M.E., Vanhoecke, B.W.A., Derycke, L., Bolca, S., Possemiers, S., Heyerick, A., Stevens, C.V., Parmar, V.S., Plant polyphenolics as anti-invasive cancer agents (2008) Anti-Cancer Agents in Medicinal Chemistry, 8 (2), pp. 171-185. , http://www.ingentaconnect.com/content/ben/acamc/2008/00000008/00000002/ art00004, DOI 10.2174/187152008783497037; Ottewell, P.D., Coleman, R.E., Holen, I., From genetic abnormality to metastases: Murine models of breast cancer and their use in the development of anticancer therapies (2006) Breast Cancer Res Treat, 96, pp. 101-113; Langley, R.R., Fidler, I.J., Tumor cell-organ microenvironment interactions in the pathogenesis of cancer metastasis (2007) Endocrine Reviews, 28 (3), pp. 297-321. , http://edrv.endojournals.org/cgi/reprint/28/3/297.pdf, DOI 10.1210/er.2006-0027; Kuperwasser, C., Chavarria, T., Wu, M., Magrane, G., Gray, J.W., Carey, L., Richardson, A., Weinberg, R.A., Reconstruction of functionally normal and malignant human breast tissues in mice (2004) Proceedings of the National Academy of Sciences of the United States of America, 101 (14), pp. 4966-4971. , DOI 10.1073/pnas.0401064101; Hoffman, R.M., Real-time subcellular imaging in live animals: New visible targets for cancer drug discovery (2006) IDrugs, 9 (9), pp. 632-635; Fomchenko, E.I., Holland, E.C., Mouse models of brain tumors and their applications in preclinical trials (2006) Clinical Cancer Research, 12 (18), pp. 5288-5297. , DOI 10.1158/1078-0432.CCR-06-0438; Gingrich, J.R., Barrios, R.J., Morton, R.A., Boyce, B.F., DeMayo, F.J., Finegold, M.J., Angelopoulou, R., Greenberg, N.M., Metastatic prostate cancer in a transgenic mouse (1996) Cancer Research, 56 (18), pp. 4096-4102; Peri, A.-K., Wilgenbus, P., Dahl, U., Semb, H., Christofori, G., A causal role for E-cadherin in the transition from adenoma to carcinoma (1998) Nature, 392 (6672), pp. 190-193. , DOI 10.1038/32433; Ambartsumian, N., Grigorian, M., Lukanidin, E., Genetically modified mouse models to study the role of metastasis-promoting S100A4(mts1) protein in metastatic mammary cancer (2005) Journal of Dairy Research, 72 (SPEC. ISS.), pp. 27-33. , DOI 10.1017/S0022029905001093; Scherer, R.L., McIntyre, J.O., Matrisian, L.M., Imaging matrix metalloproteinases in cancer (2008) Cancer Metastasis Rev, 27, pp. 679-690; Espina, V., Heiby, M., Pierobon, M., Liotta, L.A., Laser capture microdissection technology (2007) Expert Review of Molecular Diagnostics, 7 (5), pp. 647-657. , http://www.future-drugs.com/doi/pdf/10.1586/14737159.7.5.647, DOI 10.1586/14737159.7.5.647; Eccles, S.A., Welch, D.R., Metastasis: recent discoveries and novel treatment strategies (2007) Lancet, 369 (9574), pp. 1742-1757. , DOI 10.1016/S0140-6736(07)60781-8, PII S0140673607607818; Brenton, J.D., Carey, L.A., Ahmed, A., Caldas, C., Molecular classification and molecular forecasting of breast cancer: Ready for clinical application? (2005) Journal of Clinical Oncology, 23 (29), pp. 7350-7360. , DOI 10.1200/JCO.2005.03.3845; Montel, V., Huang, T.-Y., Mose, E., Pestonjamasp, K., Tarin, D., Expression profiling of primary tumors and matched lymphatic and lung metastases in a xenogeneic breast cancer model (2005) American Journal of Pathology, 166 (5), pp. 1565-1579; Karpf, A.R., Jones, D.A., Reactivating the expression of methylation silenced genes in human cancer (2002) Oncogene, 21 (35 REV. ISS. 3), pp. 5496-5503. , DOI 10.1038/sj.onc.1205602; Feng, Y., Sun, B., Li, X., Zhang, L., Niu, Y., Xiao, C., Ning, L., Hao, X., Differentially expressed genes between primary cancer and paired lymph node metastases predict clinical outcome of node-positive breast cancer patients (2007) Breast Cancer Research and Treatment, 103 (3), pp. 319-329. , DOI 10.1007/s10549-006-9385-7; Van't Veer, L.J., Dai, H., Van De Vijver, M.J., He, Y.D., Hart, A.A.M., Mao, M., Peterse, H.L., Friend, S.H., Gene expression profiling predicts clinical outcome of breast cancer (2002) Nature, 415 (6871), pp. 530-536. , DOI 10.1038/415530a; Wang, W., Klijn, J.G., Zhang, Y., Gene-expression profiles to predict distant metastasis of lymph-node-negative primary breast cancer (2005) Lancet, 415, pp. 530-536; Eckhardt, B.L., Parker, B.S., Van Laar, R.K., Restall, C.M., Natoli, A.L., Tavaria, M.D., Stanley, K.L., Anderson, R.L., Genomic analysis of a spontaneous model of breast cancer metastasis to bone reveals a role for the extracellular matrix (2005) Molecular Cancer Research, 3 (1), pp. 1-13; Adib, T.R., Henderson, S., Perrett, C., Hewitt, D., Bourmpoulia, D., Ledermann, J., Boshoff, C., Predicting biomarkers for ovarian cancer using gene-expression microarrays (2004) British Journal of Cancer, 90 (3), pp. 686-692. , DOI 10.1038/sj.bjc.6601603; Suzuki, M., Tarin, D., Gene expression profiling of human lymph node metastases and matched primary breast carcinomas: Clinical implications (2007) Molecular Oncology, 1 (2), pp. 172-180. , DOI 10.1016/j.molonc.2007.03.005, PII S1574789107000154; Chang, H.Y., Nuyten, D.S.A., Sneddon, J.B., Hastie, T., Tibshirani, R., Sorlie, T., Dai, H., Van De Vijver, M.J., Robustness, scalability, and integration of a wound-response gene expression signature in predicting breast cancer survival (2005) Proceedings of the National Academy of Sciences of the United States of America, 102 (10), pp. 3738-3743. , DOI 10.1073/pnas.0409462102; Finak, G., Bertos, N., Pepin, F., Sadekova, S., Souleimanova, M., Zhao, H., Chen, H., Park, M., Stromal gene expression predicts clinical outcome in breast cancer (2008) Nature Medicine, 14 (5), pp. 518-527. , DOI 10.1038/nm1764, PII NM1764; Clark, I.M., Swingler, T.E., Sampieri, C.L., The regulation of matrix metalloproteinases and their inhibitors (2008) Int J Biochem Cell Biol, 40, pp. 1362-1378; Li, Y., Liang, J., Kang, S., Dong, Z., Wang, N., Xing, H., Zhou, R., Zhao, X., E-cadherin gene polymorphisms and haplotype associated with the occurrence of epithelial ovarian cancer in Chinese (2008) Gynecologic Oncology, 108 (2), pp. 409-414. , DOI 10.1016/j.ygyno.2007.10.024, PII S0090825807008517; Brendle, A., Lei, H., Brandt, A., Polymorphisms in predicted microRNA-binding sites in integrin genes and breast cancer: ITGB4 as prognostic marker (2008) Carcinogenesis, 29, pp. 1394-1399; Hunter, K.W., Crawford, N.P., Germ line polymorphism in metastatic progression (2006) Cancer Research, 66 (3), pp. 1251-1254. , DOI 10.1158/0008-5472.CAN-05-3705; Crawford, N.P., Ziogas, A., Peel, D.J., Germline polymorphisms in SIPA1 are associated with metastasis and other indicators of poor prognosis in breast cancer (2006) Breast Cancer Res, 8, p. 16; Van Roy, F., Berx, G., The cell-cell adhesion molecule E-cadherin (2008) Cell Mol Life Sci, 65, pp. 3756-3788; Bartel, D.P., Chen, C.-Z., Micromanagers of gene expression: The potentially widespread influence of metazoan microRNAs (2004) Nature Reviews Genetics, 5 (5), pp. 396-400; Ma, L., Weinberg, R.A., Micromanagers of malignancy: Role of microRNAs in regulating metastasis (2008) Trends Genet, 24, pp. 448-456; Graff, J.R., Zimmer, S.G., Translational control and metastatic progression: Enhanced activity of the mRNA cap-binding protein eIF-4E selectively enhances translation of metastasis-related mRNAs (2003) Clinical and Experimental Metastasis, 20 (3), pp. 265-273. , DOI 10.1023/A:1022943419011; Hao, X., Sun, B., Hu, L., Lahdesmaki, H., Dunmire, V., Feng, Y., Zhang, S.-W., Zhang, W., Differential Gene and Protein Expression in Primary Breast Malignancies and Their Lymph Node Metastases as Revealed by Combined cDNA Microarray and Tissue Microarray Analysis (2004) Cancer, 100 (6), pp. 1110-1122. , DOI 10.1002/cncr.20095; Hakomori, S.-I., Tumor malignancy defined by aberrant glycosylation and sphingo(glyco)lipid metabolism (1996) Cancer Research, 56 (23), pp. 5309-5318; Yoshimura, M., Ihara, Y., Matsuzawa, Y., Taniguchi, N., Aberrant glycosylation of E-cadherin enhances cell-cell binding to suppress metastasis (1996) Journal of Biological Chemistry, 271 (23), pp. 13811-13815. , DOI 10.1074/jbc.271.23.13811; McLachlan, R.W., Yap, A.S., Not so simple: The complexity of phosphotyrosine signaling at cadherin adhesive contacts (2007) Journal of Molecular Medicine, 85 (6), pp. 545-554. , DOI 10.1007/s00109-007-0198-x, Special Topic: Tumor Cell Invasion and Metastasis; Wipff, P.J., Hinz, B., Integrins and the activation of latent transforming growth factor beta1-an intimate relationship (2008) Eur J Cell Biol, 87, pp. 601-615; Paredes, J., Correia, A.L., Ribeiro, A.S., P-cadherin expression in breast cancer: A review (2007) Breast Cancer Res, 9, p. 214; Van Marck, V., Stove, C., Van Den Bossche, K., Stove, V., Paredes, J., Vander Haeghen, Y., Bracke, M., P-cadherin promotes cell-cell adhesion and counteracts invasion in human melanoma (2005) Cancer Research, 65 (19), pp. 8774-8783. , DOI 10.1158/0008-5472.CAN-04-4414; Wheelock, M.J., Shintani, Y., Maeda, M., Fukumoto, Y., Johnson, K.R., Cadherin switching (2008) Journal of Cell Science, 121 (6), pp. 727-735. , DOI 10.1242/jcs.000455; De Wever, O., Westbroek, W., Verloes, A., Bloemen, N., Bracke, M., Gespach, C., Bruyneel, E., Mareel, M., Critical role of N-cadherin in myofibroblast invasion and migration in vitro stimulated by colon-cancer-cell-derived TGF-β or wounding (2004) Journal of Cell Science, 117 (20), pp. 4691-4703. , DOI 10.1242/jcs.01322; Alexander, N.R., Tran, N.L., Rekapally, H., N-cadherin gene expression in prostate carcinoma is modulated by integrin-dependent nuclear translocation of Twist1 (2006) Cancer Res, 66, pp. 3365-3369; Stove, C., Bracke, M., Roles for neuregulins in human cancer (2005) Clinical and Experimental Metastasis, 21 (8), pp. 665-684. , DOI 10.1007/s10585-004-6917-6; Kerbel, R.S., Tumor angiogenesis (2008) New England Journal of Medicine, 358 (19), pp. 2039-2049. , http://content.nejm.org/cgi/reprint/358/19/2039.pdf, DOI 10.1056/NEJMra0706596; Chabottaux, V., Noel, A., Breast cancer progression: Insights into multifaceted matrix metalloproteinases (2007) Clinical and Experimental Metastasis, 24 (8), pp. 647-656. , DOI 10.1007/s10585-007-9113-7; Noel, A., Jost, M., Maquoi, E., Matrix metalloproteinases at cancer tumor-host interface (2008) Seminars in Cell and Developmental Biology, 19 (1), pp. 52-60. , DOI 10.1016/j.semcdb.2007.05.011, PII S1084952107000821, Matrix Metalloproteinases; Jones, R.B., Gordus, A., Krall, J.A., MacBeath, G., A quantitative protein interaction network for the ErbB receptors using protein microarrays (2006) Nature, 439 (7073), pp. 168-174. , DOI 10.1038/nature04177, PII NATURE04177; Pawson, T., Nash, P., Assembly of cell regulatory systems through protein interaction domains (2003) Science, 300 (5618), pp. 445-452. , DOI 10.1126/science.1083653; Kopfstein, L., Christofori, G., Metastasis: Cell-autonomous mechanisms versus contributions by the tumor microenvironment (2006) Cell Mol Life Sci, 63, pp. 449-468; Paget, S., The distribution of secondary growths in cancer of the breast (1889) Lancet, 1, pp. 571-573; Mareel, M.M., Behrens, J., Birchmeier, W., Down-regulation of E-cadherin expression in Madin Darby canine kidney (MDCK) cells inside tumors of nude mice (1991) Int J Cancer, 47, pp. 922-928; Creighton, C.J., Bromberg-White, J.L., Misek, D.E., Monsma, D.J., Brichory, F., Kuick, R., Giordano, T.J., Hanash, S.M., Analysis of tumor-host interactions by gene expression profiling of lung adenocarcinoma xenografts identifies genes involved in tumor formation (2005) Molecular Cancer Research, 3 (3), pp. 119-129. , DOI 10.1158/1541-7786.MCR-04-0189; Dimanche-Boitrel, M.T., Vakaet Jr., L., Pujuguet, P., Chauffert, B., Martin, M.S., Hammann, A., Van Roy, F., Martin, F., In vivo and in vitro invasiveness of a rat colon-cancer cell line maintaining E-cadherin expression: An enhancing role of tumor-associated myofibroblasts (1994) International Journal of Cancer, 56 (4), pp. 512-521; Lin, E.Y., Pollard, J.W., Tumor-associated macrophages press the angiogenic switch in breast cancer (2007) Cancer Research, 67 (11), pp. 5064-5066. , http://cancerres.aacrjournals.org/cgi/reprint/67/11/5064, DOI 10.1158/0008-5472.CAN-07-0912; Korc, M., Pancreatic cancer-associated stroma production (2007) Am J sur, 194 (4 SUPPL.), pp. 84-S86; He, Y., Rajantie, I., Pajusola, K., Jeltsch, M., Holopainen, T., Yla-Herttuala, S., Harding, T., Alitalo, K., Vascular endothelial cell growth factor receptor 3-mediated activation of lymphatic endothelium is crucial for tumor cell entry and spread via lymphatic vessels (2005) Cancer Research, 65 (11), pp. 4739-4746. , DOI 10.1158/0008-5472.CAN-04-4576; Mahabeleshwar, G.H., Byzova, T.V., Angiogenesis in Melanoma (2007) Seminars in Oncology, 34 (6), pp. 555-565. , DOI 10.1053/j.seminoncol.2007.09.009, PII S0093775407001832, Malignant Melanoma; Benoy, I.H., Salgado, R., Elst, H., Relative microvessel area of the primary tumour, and not lymph node status, predicts the presence of bone marrow micrometastases detected by reverse transcriptase polymerase chain reaction in patients with clinically non-metastatic breast cancer (2005) Breast Cancer Res, 7, pp. 210-R219; Hicklin, D.J., Ellis, L.M., Role of the vascular endothelial growth factor pathway in tumor growth and angiogenesis (2005) Journal of Clinical Oncology, 23 (5), pp. 1011-1027. , DOI 10.1200/JCO.2005.06.081; Schoppmann, S.F., Bayer, G., Aumayr, K., Taucher, S., Geleff, S., Rudas, M., Kubista, E., Horvat, R., Prognostic value of lymphangiogenesis and lymphovascular invasion in invasive breast cancer (2004) Annals of Surgery, 240 (2), pp. 306-312. , DOI 10.1097/01.sla.0000133355.48672.22; Tobler, N.E., Detmar, M., Tumor and lymph node lymphangiogenesis - Impact on cancer metastasis (2006) Journal of Leukocyte Biology, 80 (4), pp. 691-696. , http://www.jleukbio.org/cgi/reprint/80/4/691, DOI 10.1189/jlb.1105653; Nathanson, S.D., Leong, S., Preclinical models of regional lymph node tumor metastasis (2007) Cancer Metastasis and the Lymphvascular System: Basis for Rational Therapy, pp. 129-156. , Springer New York; Wissmann, C., Detmar, M., Pathways targeting tumor lymphangiogenesis (2006) Clinical Cancer Research, 12 (23), pp. 6865-6868. , DOI 10.1158/1078-0432.CCR-06-1800; Rafii, D.C., Psaila, B., Butler, J., Jin, D.K., Lyden, D., Regulation of vasculogenesis by platelet-mediated recruitment of bone marrow-derived cells (2008) Arteriosclerosis, Thrombosis, and Vascular Biology, 28 (2), pp. 217-222. , DOI 10.1161/ATVBAHA.107.151159, PII 0004360520080200000004; Mantovani, A., Sica, A., Sozzani, S., Allavena, P., Vecchi, A., Locati, M., The chemokine system in diverse forms of macrophage activation and polarization (2004) Trends in Immunology, 25 (12), pp. 677-686. , DOI 10.1016/j.it.2004.09.015, PII S1471490604002959; Mantovani, A., Romero, P., Palucka, A.K., Tumour immunity: Effector response to tumour and role of the microenvironment (2008) Lancet, 371, pp. 771-783; Talmadge, J.E., Donkor, M., Scholar, E., Inflammatory cell infiltration of tumors: Jekyll or Hyde (2007) Cancer and Metastasis Reviews, 26 (3-4), pp. 373-400. , DOI 10.1007/s10555-007-9072-0, Forty Years of Metastasis Research: A Tribute to Dr. Isaiah J. Fidler; Lewis, C.E., Pollard, J.W., Distinct role of macrophages in different tumor microenvironments (2006) Cancer Research, 66 (2), pp. 605-612. , DOI 10.1158/0008-5472.CAN-05-4005; Condeelis, J., Pollard, J.W., Macrophages: Obligate partners for tumor cell migration, invasion, and metastasis (2006) Cell, 124 (2), pp. 263-266. , DOI 10.1016/j.cell.2006.01.007, PII S0092867406000559; Wyckoff, J.B., Wang, Y., Lin, E.Y., Li, J.-F., Goswami, S., Stanley, E.R., Segall, J.E., Condeelis, J., Direct visualization of macrophage-assisted tumor cell intravasation in mammary tumors (2007) Cancer Research, 67 (6), pp. 2649-2656. , DOI 10.1158/0008-5472.CAN-06-1823; Mahadevan, D., Von Hoff, D.D., Tumor-stroma interactions in pancreatic ductal adenocarcinoma (2007) Molecular Cancer Therapeutics, 6 (4), pp. 1186-1197. , DOI 10.1158/1535-7163.MCT-06-0686; De Wever, O., Demetter, P., Mareel, M., Stromal myofibroblasts are drivers of invasive cancer growth (2008) Int J Cancer, 123, pp. 2229-2238; Massaguè, J., TGFbeta in cancer (2008) Cell, 134, pp. 215-230; Hu, M., Yao, J., Carroll, D.K., Weremowicz, S., Chen, H., Carrasco, D., Richardson, A., Polyak, K., Regulation of In Situ to Invasive Breast Carcinoma Transition (2008) Cancer Cell, 13 (5), pp. 394-406. , DOI 10.1016/j.ccr.2008.03.007, PII S1535610808000913; Lerwill, M.F., Current practical applications of diagnostic immunohistochemistry in breast pathology (2004) American Journal of Surgical Pathology, 28 (8), pp. 1076-1091. , DOI 10.1097/01.pas.0000126780.10029.f0; Allinen, M., Beroukhim, R., Cai, L., Brennan, C., Lahti-Domenici, J., Huang, H., Porter, D., Polyak, K., Molecular characterization of the tumor microenvironment in breast cancer (2004) Cancer Cell, 6 (1), pp. 17-32. , DOI 10.1016/j.ccr.2004.06.010, PII S1535610804001783; Hu, M., Yao, J., Cai, L., Bachman, K.E., Van Den Brule, F., Velculescu, V., Polyak, K., Distinct epigenetic changes in the stromal cells of breast cancers (2005) Nature Genetics, 37 (8), pp. 899-905. , DOI 10.1038/ng1596; Barsky, S.H., Karlin, N.J., Myoepithelial cells: Autocrine and paracrine suppressors of breast cancer progression (2005) J Mammary Gland Biol Neoplasia, 10, pp. 249-260; Polyak, K., Hu, M., Do myoepithelial cells hold the key for breast tumor progression? (2005) J Mammary Gland Biol Neoplasia, 10, pp. 231-247; Mantyh, P.W., Clohisy, D.R., Koltzenburg, M., Hunt, S.P., Molecular mechanisms of cancer pain (2002) Nature Reviews Cancer, 2 (3), pp. 201-209; Ayala, G.E., Dai, H., Powell, M., Cancer-related axonogenesis and neurogenesis in prostate cancer (2008) Clin Cancer Res, 14, pp. 7593-7603; Wang, W., Zhao, H., Zhang, S., Al, E., Patterns of expression and function of the p75(NGFR) protein in pancreatic cancer cells and tumours (2008) Eur J Surg Oncol, , Nov 26 (in press); Marchesi, F., Piemonti, L., Fedele, G., The chemokine receptor CX3CR1 is involved in the neural tropism and malignant behavior of pancreatic ductal adenocarcinoma (2008) Cancer Res, 68, pp. 9060-9069; Zhang, S., Qi, L., Li, M., Chemokine CXCL12 and its receptor CXCR4 expression are associated with perineural invasion of prostate cancer (2008) J Exp Clin Cancer Res, 27, p. 62; Andarawewa, K.L., Motrescu, E.R., Chenard, M.-P., Gansmuller, A., Stoll, I., Tomasetto, C., Rio, M.-C., Stromelysin-3 is a potent negative regulator of adipogenesis participating to cancer cell-adipocyte interaction/crosstalk at the tumor invasive front (2005) Cancer Research, 65 (23), pp. 10862-10871. , DOI 10.1158/0008-5472.CAN-05-1231; Caers, J., Van Valckenborgh, E., Menu, E., Unraveling the biology of multiple myeloma disease: Cancer stem cells, acquired intracellular changes and interactions with the surrounding micro-environment (2008) Bull Cancer, 95, pp. 301-313; Vona-Davis, L., Rose, D.P., Adipokines as endocrine, paracrine, and autocrine factors in breast cancer risk and progression (2007) Endocrine-Related Cancer, 14 (2), pp. 189-206. , DOI 10.1677/ERC-06-0068; Kunduzova, O., Alet, N., Delesque-Touchard, N., Apelin/APJ signaling system: A potential link between adipose tissue and endothelial angiogenic processes (2008) FASEB J, 22, pp. 4146-4153; Cirillo, D., Rachiglio, A.M., La Montagna, R., Leptin signaling in breast cancer: An overview (2008) J Cell Biochem, 105, pp. 956-964; Jaffe, T., Schwartz, B., Leptin promotes motility and invasiveness in human colon cancer cells by activating multiple signal-transduction pathways (2008) Int J Cancer, 123, pp. 2543-2556; Horiguchi, A., Sumitomo, M., Asakuma, J., Asano, T., Zheng, R., Asano, T., Nanus, D.M., Hayakawa, M., Leptin Promotes Invasiveness of Murine Renal Cancer Cells Via Extracellular Signal-Regulated Kinases and Rho Dependent Pathway (2006) Journal of Urology, 176 (4), pp. 1636-1641. , DOI 10.1016/j.juro.2006.06.040, PII S0022534706014169; Bussard, K.M., Gay, C.V., Mastro, A.M., The bone microenvironment in metastasis; What is special about bone? (2008) Cancer Metastasis Rev, 27, pp. 41-55; Vakaet, L.A.M.-L., Boterberg, T., Pain control by ionizing radiation of bone metastasis (2004) International Journal of Developmental Biology, 48 (5-6), pp. 599-606. , DOI 10.1387/ijdb.041817lv, Invasion in Cancer and Embryonic Development; Oliveira, M.J., Van Damme, J., Lauwaet, T., De Corte, V., De Bruyne, G., Verschraegen, G., Vaneechoutte, M., Leroy, A., β-casein-derived peptides, produced by bacteria, stimulate cancer cell invasion and motility (2003) EMBO Journal, 22 (22), pp. 6161-6173. , DOI 10.1093/emboj/cdg586; Oliveira, M.J., Costa, A.C., Costa, A.M., Henriques, L., Suriano, G., Atherton, J.C., Machado, J.C., Figueiredo, C., Helicobacter pylori induces gastric epithelial cell invasion in a c-Met and type IV secretion system-dependent manner (2006) Journal of Biological Chemistry, 281 (46), pp. 34888-34896. , http://www.jbc.org/cgi/reprint/281/46/34888, DOI 10.1074/jbc.M607067200; Oliveira, M.J., Costa, A.M., Costa, A.C., Al, E., CagA associates with c-Met, E-cadherin, and p120-catenin in a multiproteic complex that suppresses Helicobacter pylori-induced cell invasive phenotype (2009) J Infect Dis, , in press; Miller, M.J., Wei, S.H., Parker, I., Cahalan, M.D., Two-photon imaging of lymphocyte motility and antigen response in intact lymph node (2002) Science, 296 (5574), pp. 1869-1873. , DOI 10.1126/science.1070051; Mullen, J.T., Wang, H., Yao, J.C., Carcinoid tumors of the duodenum (2005) Surgery, 138, pp. 971-977; Hoon, D.S.B., Kitago, M., Kim, J., Mori, T., Piris, A., Szyfelbein, K., Mihm Jr., M.C., Pantel, K., Molecular mechanisms of metastasis (2006) Cancer and Metastasis Reviews, 25 (2), pp. 203-220. , DOI 10.1007/s10555-006-8500-x; Muller, A., Homey, B., Soto, H., Ge, N., Catron, D., Buchanan, M.E., McClanahan, T., Zlotnik, A., Involvement of chemokine receptors in breast cancer metastasis (2001) Nature, 410 (6824), pp. 50-56. , DOI 10.1038/35065016; Hirakawa, S., Brown, L.F., Kodama, S., Paavonen, K., Alitalo, K., Detmar, M., VEGF-C-induced lymphangiogenesis in sentinel lymph nodes promotes tumor metastasis to distant sites (2007) Blood, 109 (3), pp. 1010-1017. , http://www.bloodjournal.org/cgi/reprint/109/3/1010, DOI 10.1182/blood-2006-05-021758; Van Den Eynden, G.G., Vandenberghe, M.K., Van Dam, P.-J.H., Colpaert, C.G., Van Dam, P., Dirix, L.Y., Vermeulen, P.B., Van Marck, E.A., Increased sentinel lymph node lymphangiogenesis is associated with nonsentinel axillary lymph node involvement in breast cancer patients with a positive sentinel node (2007) Clinical Cancer Research, 13 (18), pp. 5391-5397. , http://clincancerres.aacrjournals.org/cgi/reprint/13/18/5391, DOI 10.1158/1078-0432.CCR-07-1230; Dimeo, T.A., Kuperwasser, C., The evolving paradigm of tissue-specific metastasis (2006) Breast Cancer Res, 8, p. 301; Andre, F., Cabioglu, N., Assi, H., Sabourin, J.C., Delaloge, S., Sahin, A., Broglio, K., Cristofanilli, M., Expression of chemokine receptors predicts the site of metastatic relapse in patients with axillary node positive primary breast cancer (2006) Annals of Oncology, 17 (6), pp. 945-951. , DOI 10.1093/annonc/mdl053; Stessels, F., Van Den Eynden, G., Van Der Auwera, I., Salgado, R., Van Den Heuvel, E., Harris, A.L., Jackson, D.G., Vermeulen, P.B., Breast adenocarcinoma liver metastases, in contrast to colorectal cancer liver metastases, display a non-angiogenic growth pattern that preserves the stroma and lacks hypoxia (2004) British Journal of Cancer, 90 (7), pp. 1429-1436. , DOI 10.1038/sj.bjc.6601727; Mendes, O., Kim, H.-T., Lungu, G., Stoica, G., MMP2 role in breast cancer brain metastasis development and its regulation by TIMP2 and ERK1/2 (2007) Clinical and Experimental Metastasis, 24 (5), pp. 341-351. , DOI 10.1007/s10585-007-9071-0; Kaplan, R.N., Psaila, B., Lyden, D., Bone marrow cells in the 'pre-metastatic niche': Within bone and beyond (2006) Cancer and Metastasis Reviews, 25 (4), pp. 521-529. , DOI 10.1007/s10555-006-9036-9, Special issue on Bone Metastasis and Cancer; Hiratsuka, S., Watanabe, A., Aburatani, H., Maru, Y., Tumour-mediated upregulation of chemoattractants and recruitment of myeloid cells predetermines lung metastasis (2006) Nature Cell Biology, 8 (12), pp. 1369-1375. , DOI 10.1038/ncb1507, PII NCB1507; Kaplan, R.N., Psaila, B., Lyden, D., Niche-to-niche migration of bone-marrow-derived cells (2007) Trends in Molecular Medicine, 13 (2), pp. 72-81. , DOI 10.1016/j.molmed.2006.12.003, PII S1471491406002681; Pantel, K., Brakenhoff, R.H., Dissecting the metastatic cascade (2004) Nature Reviews Cancer, 4 (6), pp. 448-456; Vincent-Salomon, A., Bidard, F.C., Pierga, J.Y., Bone marrow micrometastasis in breast cancer: Review of detection methods, prognostic impact and biological issues (2008) Journal of Clinical Pathology, 61 (5), pp. 570-576. , DOI 10.1136/jcp.2007.046649; Bidard, F.C., Vincent-Salomon, A., Gomme, S., Disseminated tumor cells of breast cancer patients: A strong prognostic factor for distant and local relapse (2008) Clin Cancer Res, 14, pp. 3306-3311. , Institut Curie Breast Cancer Study Group et al; Ceelen, W.P., Bracke, M.E., Peritoneal minimal residual disease in colorectal cancer: Mechanisms, prevention, and treatment (2009) Lancet Oncol, 10, pp. 72-79; Bidard, F.C., Pierga, J.Y., Vincent-Salomon, A., A "class action" against the microenvironment: Do cancer cells cooperate in metastasis? (2008) Cancer Metastasis Rev, 27, pp. 5-10; Bertolini, F., Mancuso, P., Shaked, Y., Kerbel, R.S., Molecular and cellular biomarkers for angiogenesis in clinical oncology (2007) Drug Discovery Today, 12 (19-20), pp. 806-812. , DOI 10.1016/j.drudis.2007.08.011, PII S1359644607003534; Shields, J.D., Fleury, M.E., Yong, C., Tomei, A.A., Randolph, G.J., Swartz, M.A., Autologous Chemotaxis as a Mechanism of Tumor Cell Homing to Lymphatics via Interstitial Flow and Autocrine CCR7 Signaling (2007) Cancer Cell, 11 (6), pp. 526-538. , DOI 10.1016/j.ccr.2007.04.020, PII S1535610807001456; Nierodzik, M.L., Karpatkin, S., Thrombin induces tumor growth, metastasis, and angiogenesis: Evidence for a thrombin-regulated dormant tumor phenotype (2006) Cancer Cell, 10 (5), pp. 355-362. , DOI 10.1016/j.ccr.2006.10.002, PII S1535610806002868; Podsypanina, K., Du, Y.C., Jechlinger, M., Seeding and propagation of untransformed mouse mammary cells in the lung (2008) Science, 321, pp. 1841-1844; Aguirre-Ghiso, J.A., Models, mechanisms and clinical evidence for cancer dormancy (2007) Nature Reviews Cancer, 7 (11), pp. 834-846. , DOI 10.1038/nrc2256, PII NRC2256; Brackstone, M., Townson, J.L., Chambers, A.F., Tumour dormancy in breast cancer: An update (2007) Breast Cancer Res, 9, p. 208; O'Reilly, M.S., Holmgren, L., Shing, Y., Chen, C., Rosenthal, R.A., Moses, M., Lane, W.S., Folkman, J., Angiostatin: A novel angiogenesis inhibitor that mediates the suppression of metastases by a Lewis lung carcinoma (1994) Cell, 79 (2), pp. 315-328. , DOI 10.1016/0092-8674(94)90200-3; Norton, L., Massague, J., Is cancer a disease of self-seeding? (2006) Nature Medicine, 12 (8), pp. 875-878. , DOI 10.1038/nm0806-875, PII NM0806875; Bidard, F.C., (2008) Interactions en CoopéRations Cellulaires dans le Processus Métastatique, , MSc thesis. L'Université Paris XI; Benvenuti, S., Comoglio, P.M., The MET receptor tyrosine kinase in invasion and metastasis (2007) Journal of Cellular Physiology, 213 (2), pp. 316-325. , DOI 10.1002/jcp.21183; Mareel, M., Leroy, A., Clinical, cellular, and molecular aspects of cancer invasion (2003) Physiological Reviews, 83 (2), pp. 337-376; Christofori, G., New signals from the invasive front (2006) Nature, 441 (7092), pp. 444-450. , DOI 10.1038/nature04872, PII NATURE04872; Sabbah, M., Emami, S., Redeuilh, G., Molecular signature and therapeutic perspective of the epithelial-to-mesenchymal transitions in epithelial cancers (2008) Drug Resist Updat, 11, pp. 123-151; Thiery, J.P., Sleeman, J.P., Complex networks orchestrate epithelial-mesenchymal transitions (2006) Nature Reviews Molecular Cell Biology, 7 (2), pp. 131-142. , DOI 10.1038/nrm1835, PII NRM1835; Yang, J., Weinberg, R.A., Epithelial-Mesenchymal Transition: At the Crossroads of Development and Tumor Metastasis (2008) Developmental Cell, 14 (6), pp. 818-829. , DOI 10.1016/j.devcel.2008.05.009, PII S1534580708002098; Christiansen, J.J., Rajasekaran, A.K., Reassessing epithelial to mesenchymal transition as a prerequisite for carcinoma invasion and metastasis (2006) Cancer Research, 66 (17), pp. 8319-8326. , DOI 10.1158/0008-5472.CAN-06-0410; Brabletz, T., Jung, A., Spaderna, S., Hlubek, F., Kirchner, T., Migrating cancer stem cells - An integrated concept of malignant tumour progression (2005) Nature Reviews Cancer, 5 (9), pp. 744-749. , DOI 10.1038/nrc1694, PII N1694; Tarin, D., The fallacy of epithelial mesenchymal transition in neoplasia (2005) Cancer Research, 65 (14), pp. 5996-6000. , DOI 10.1158/0008-5472.CAN-05-0699; Garber, K., Epithelial-to-mesenchymal transition is important to metastasis, but questions remain (2008) J Natl Cancer Inst, 100, pp. 232-239; De Wever, O., Derycke, L., Hendrix, A., De Meerleer, G., Godeau, F., Depypere, H., Bracke, M., Soluble cadherins as cancer biomarkers (2007) Clinical and Experimental Metastasis, 24 (8), pp. 685-697. , DOI 10.1007/s10585-007-9104-8; Bellahcene, A., Castronovo, V., Ogbureke, K.U.E., Fisher, L.W., Fedarko, N.S., Small integrin-binding ligand N-linked glycoproteins (SIBLINGs): Multifunctional proteins in cancer (2008) Nature Reviews Cancer, 8 (3), pp. 212-226. , DOI 10.1038/nrc2345, PII NRC2345; Gimona, M., Buccione, R., Adhesions that mediate invasion (2006) International Journal of Biochemistry and Cell Biology, 38 (11), pp. 1875-1892. , DOI 10.1016/j.biocel.2006.05.003, PII S1357272506001580; Gimona, M., Buccione, R., Courtneidge, S.A., Assembly and biological role of podosomes and invadopodia (2008) Curr Opin Cell Biol, 20, pp. 235-241; Lopez-Otin, C., Matrisian, L.M., Emerging roles of proteases in tumour suppression (2007) Nature Reviews Cancer, 7 (10), pp. 800-808. , DOI 10.1038/nrc2228, PII NRC2228; Martin, M.D., Matrisian, L.M., The other side of MMPs: Protective roles in tumor progression (2007) Cancer and Metastasis Reviews, 26 (3-4), pp. 717-724. , DOI 10.1007/s10555-007-9089-4, Forty Years of Metastasis Research: A Tribute to Dr. Isaiah J. Fidler; Sahai, E., Mechanisms of cancer cell invasion (2005) Current Opinion in Genetics and Development, 15 (1), pp. 87-96. , DOI 10.1016/j.gde.2004.12.002, PII S0959437X04001881, Oncogenes and Cell Proliferation; Wolf, K., Mazo, I., Leung, H., Engelke, K., Von Andrian, U.H., Deryugina, E.I., Strongin, A.Y., Friedl, P., Compensation mechanism in tumor cell migration: Mesenchymal-amoeboid transition after blocking of pericellular proteolysis (2003) Journal of Cell Biology, 160 (2), pp. 267-277. , DOI 10.1083/jcb.200209006; Wolf, K., Friedl, P., Molecular mechanisms of cancer cell invasion and plasticity (2006) Br J Dermatol, 154 (SUPPL. 1), pp. 11-15; Yilmaz, M., Christofori, G., Lehembre, F., Distinct mechanisms of tumor invasion and metastasis (2007) Trends in Molecular Medicine, 13 (12), pp. 535-541. , DOI 10.1016/j.molmed.2007.10.004, PII S1471491407001888; Wicki, A., Christofori, G., The potential role of podoplanin in tumour invasion (2007) British Journal of Cancer, 96 (1), pp. 1-5. , DOI 10.1038/sj.bjc.6603518, PII 6603518; Yamaguchi, H., Condeelis, J., Regulation of the actin cytoskeleton in cancer cell migration and invasion (2007) Biochimica et Biophysica Acta - Molecular Cell Research, 1773 (5), pp. 642-652. , DOI 10.1016/j.bbamcr.2006.07.001, PII S0167488906001558; Sahai, E., Garcia-Medina, R., Pouyssegur, J., Vial, E., Smurf1 regulates tumor cell plasticity and motility through degradation of RhoA leading to localized inhibition of contractility (2007) Journal of Cell Biology, 176 (1), pp. 35-42. , http://www.jcb.org/cgi/reprint/176/1/35, DOI 10.1083/jcb.200605135; Gentile, A., Trusolino, L., Comoglio, P.M., The Met tyrosine kinase receptor in development and cancer (2008) Cancer Metastasis Rev, 27, pp. 85-94; Lengyel, E., Sawada, K., Salgia, R., Tyrosine kinase mutations in human cancer (2007) Current Molecular Medicine, 7 (1), pp. 77-84. , http://www.ingentaconnect.com/content/ben/cmm/2007/00000007/00000001/ art00007, DOI 10.2174/156652407779940486; Funasaka, T., Raz, A., The role of autocrine motility factor in tumor and tumor microenvironment (2007) Cancer and Metastasis Reviews, 26 (3-4), pp. 725-735. , DOI 10.1007/s10555-007-9086-7, Forty Years of Metastasis Research: A Tribute to Dr. Isaiah J. Fidler; Hehlgans, S., Haase, M., Cordes, N., Signalling via integrins: Implications for cell survival and anticancer strategies (2007) Biochimica et Biophysica Acta - Reviews on Cancer, 1775 (1), pp. 163-180. , DOI 10.1016/j.bbcan.2006.09.001, PII S0304419X06000588; Douma, S., Van Laar, T., Zevenhoven, J., Suppression of anoikis and induction of metastasis by the neurotrophic receptor TrkB (2004) Nature, 430, pp. 1034-1039; Geiger, T.R., Peeper, D.S., The neurotrophic receptor TrkB in anoikis resistance and metastasis: A perspective (2005) Cancer Research, 65 (16), pp. 7033-7036. , DOI 10.1158/0008-5472.CAN-05-0709; Sandri, M.T., Circulating tumor cells (2007) IEO-Scientific Report 2007-ongoing Research 2008, pp. 192-194; Gnerlich, J., Jeffe, D.B., Deshpande, A.D., Beers, C., Zander, C., Margenthaler, J.A., Surgical removal of the primary tumor increases overall survival in patients with metastatic breast cancer: Analysis of the 1988-2003 SEER data (2007) Annals of Surgical Oncology, 14 (8), pp. 2187-2194. , DOI 10.1245/s10434-007-9438-0; Salama, J.K., Chmura, S.J., Mehta, N., An initial report of a radiation dose-escalation trial in patients with one to five sites of metastatic disease (2008) Clin Cancer Res, 14, pp. 5255-5259; Dolle, L., Depypere, H.T., Bracke, M.E., Anti-invasive and anti-metastasis strategies: New roads, new tools and new hopes (2006) Current Cancer Drug Targets, 6 (8), pp. 729-751. , http://docstore.ingenta.com/cgi-bin/ds_deliver/1/u/d/ISIS/33724480.1/ben/ ccdt/2006/00000006/00000008/art00007/9C146EDF9740EFD9116485319359E89FF5E8D1E22C. pdf?link=http://www.ingentaconnect.com/error/delivery&format=pdf, DOI 10.2174/156800906779010263; Fox, S.B., Generali, D.G., Harris, A.L., Breast tumour angiogenesis (2007) Breast Cancer Res, 9, p. 216; Shaked, Y., Kerbel, R.S., Antiangiogenic strategies on defense: On the possibility of blocking rebounds by the tumor vasculature after chemotherapy (2007) Cancer Research, 67 (15), pp. 7055-7058. , http://cancerres.aacrjournals.org/cgi/reprint/67/15/7055, DOI 10.1158/0008-5472.CAN-07-0905; Formenti, S.C., Demaria, S., Local control by radiotherapy: Is that all there is? (2008) Breast Cancer Res, 10, p. 215; Husemann, Y., Geigl, J.B., Schubert, F., Musiani, P., Meyer, M., Burghart, E., Forni, G., Klein, C.A., Systemic Spread Is an Early Step in Breast Cancer (2008) Cancer Cell, 13 (1), pp. 58-68. , DOI 10.1016/j.ccr.2007.12.003, PII S1535610807003728; Denys, H., Derycke, L., Hendrix, A., Differential impact of TGF-beta and EGF on fibroblast differentiation and invasion reciprocally promotes colon cancer cell invasion (2008) Cancer Lett, 266, pp. 263-274; Milas, L., Mason, K., Liao, Z., Nieder, C., Milas, L., Ang, K.K., Role of cyclooxygenase-2 (COX-2) and its inhibition in tumor biology and radiotherapy (2003) Modification of Radiation Response, pp. 241-258. , Springer Berlin; Opdenakker, G., Van Damme, J., The countercurrent principle in invasion and metastasis of cancer cells. Recent insights on the roles of chemokines (2004) International Journal of Developmental Biology, 48 (5-6), pp. 519-527. , DOI 10.1387/ijdb.041796go, Invasion in Cancer and Embryonic Development; Nugent, J.L., Bunn Jr., P.A., Matthews, M.J., CNS metastases in small cell bronchogenic carcinoma. Increasing frequency and changing pattern with lengthening survival (1979) Cancer, 44 (5), pp. 1885-1893; Camphausen, K., Moses, M.A., Beecken, W.-D., Khan, M.K., Folkman, J., O'Reilly, M.S., Radiation therapy to a primary tumor accelerates metastatic growth in mice (2001) Cancer Research, 61 (5), pp. 2207-2211; Ramaswamy, S., Ross, K.N., Lander, E.S., Golub, T.R., A molecular signature of metastasis in primary solid tumors (2003) Nature Genetics, 33 (1), pp. 49-54. , DOI 10.1038/ng1060; Chen, Y.-J., Lin, S.-C., Kao, T., Chang, C.-S., Hong, P.-S., Shieh, T.-M., Chang, K.-W., Genome-wide profiling of oral squamous cell carcinoma (2004) Journal of Pathology, 204 (3), pp. 326-332. , DOI 10.1002/path.1640; Perou, C.M., Sorile, T., Eisen, M.B., Van De Rijn, M., Jeffrey, S.S., Ress, C.A., Pollack, J.R., Botstein, D., Molecular portraits of human breast tumours (2000) Nature, 406 (6797), pp. 747-752. , DOI 10.1038/35021093; LaTulippe, E., Satagopan, J., Smith, A., Scher, H., Scardino, P., Reuter, V., Gerald, W.L., Comprehensive gene expression analysis of prostate cancer reveals distinct transcriptional programs associated with metastatic disease (2002) Cancer Research, 62 (15), pp. 4499-4506; Lapointe, J., Li, C., Giacomini, C.P., Salari, K., Huang, S., Wang, P., Ferrari, M., Pollack, J.R., Genomic profiling reveals alternative genetic pathways of prostate tumorigenesis (2007) Cancer Research, 67 (18), pp. 8504-8510. , http://cancerres.aacrjournals.org/cgi/reprint/67/18/8504, DOI 10.1158/0008-5472.CAN-07-0673; Lips, E.H., Van Eijk, R., De Graaf, E.J., Integrating chromosomal aberrations and gene expression profiles to dissect rectal tumorigenesis (2008) BMC Cancer, 8, p. 314; Cromer, A., Carles, A., Millon, R., Ganguli, G., Chalmel, F., Lemaire, F., Young, J., Wasylyk, B., Identification of genes associated with tumorigenesis and metastatic potential of hypopharyngeal cancer by microarray analysis (2004) Oncogene, 23 (14), pp. 2484-2498. , DOI 10.1038/sj.onc.1207345; Couvelard, A., Hu, J., Steers, G., O'Toole, D., Sauvanet, A., Belghiti, J., Bedossa, P., Pezzella, F., Identification of Potential Therapeutic Targets by Gene-Expression Profiling in Pancreatic Endocrine Tumors (2006) Gastroenterology, 131 (5), pp. 1597-1610. , DOI 10.1053/j.gastro.2006.09.007, PII S0016508506020014; Bertucci, F., Finetti, P., Rougemont, J., Charafe-Jauffret, E., Nasser, V., Loriod, B., Camerlo, J., Viens, P., Gene expression profiling for molecular characterization of inflammatory breast cancer and prediction of response to chemotherapy (2004) Cancer Research, 64 (23), pp. 8558-8565. , DOI 10.1158/0008-5472.CAN-04-2696
Keywords: bone marrow; cancer cell; cancer invasion; carcinogenesis; cell activity; Circulation; ecosystem; epigenetics; extracellular matrix; gene control; host cell; human; Humans; lymph node metastasis; metastasis; Metastatic site; microarray analysis; Molecular biology; molecular imaging; Neoplasm Invasiveness; Neoplasm Metastasis; Neoplasms; nonhuman; pleiotropy; primary tumor; priority journal; Promoter and suppressor genes; promoter region; review; signal transduction; suppressor gene; Therapy guidance; Tumor-associated host cells

Cationic liposome-DNA complexes as gene delivery vectors: Development and behaviour towards bone-like cells - Oliveira, A.C.; Ferraz, M.P.; Monteiro, F.J.; Simões, S. (Acta BiomaterialiaActa Biomater., 2009)
Modulation of the biological pathways responsible for fracture repair and osteogenisis may accelerate regeneration. Gene therapy is an alternative method for the release of osteogenisis-stimulating proteins into tissues. The development of vectors for gene release is still a problem in terms of ethics and techniques. In this work we evaluated whether cationic liposomes constitute a valuable strategy for the release of genetic material into bone tissue cells as non-viral vectors. Liposomes were prepared with 1,2-dioleoyl-3-trimethylammonium propane (DOTAP)-2-dioleoyl-sn-glycero-3-phosphatidylethanolamine and DOTAP-cholesterol, and characterized according to their size, zeta potential, DNA protection capacity and cytotoxicity. Transfection studies were also carried out using pCMVβ-gal plasmid in two osteoblastic cell lines (MG63 and MC3T3-E1) and in the 294T line, varying the charge ratio and the applied DNA dose. Inclusion of transferrin to increase the expression was also tested. The results suggest that there is great dependency between the transfection activity and the lipid formulation, the charge ratios of the complexes, the applied DNA dose and the cell type. There were even some differences concerning both osteoblastic lines under study. The cells of the MC3T3-E1 line present greater expression levels than the cells of the MG-63 line. The conjugation of the transferrin with the complexes contributes to the increase in transfection levels, possibly due to an increase in internalization of complexes. It is thus a good strategy for inducing the expression of specific genes in osteoblast-like cells. © 2009 Acta Materialia Inc.
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.02.019PubMed ID: 19332382Language of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; CEBIMED, Faculdade de Ciências da Saú, Universidade Fernando Pessoa, Rua Carlos da Maia, 296, 4200-150 Porto, Portugal; email: mpferraz@ufp.ptChemicals/CAS: 1,2 dioleoyl 3 trimethylammoniopropane, 144189-73-1; DNA, 9007-49-2; transferrin, 82030-93-1; DNA, 9007-49-2; LiposomesReferences: Luo, J., Sun, M.H., Kang, Q., Peng, Y., Jiang, W., Luu, H.H., Gene therapy for bone regeneration (2005) Curr Gene Ther, 5 (2), pp. 167-179;Oreffo, R.O.C., Triffitt, J.T., Future potentials for using osteogenic stem cells and biomaterials in orthopedics (1999) Bone, 25 (2 SUPPL. 1), pp. 5S-9S; Laurencin, C.T., Attawia, M.A., Lu, L.Q., Borden, M.D., Lu, H.H., Gorum, W.J., Poly(lactide-co-glycolide)/hydroxyapatite delivery of BMP-2-producing cells: a regional gene therapy approach to bone regeneration (2001) Biomaterials, 22 (11), pp. 1271-1277; Katz, J.L., (1996) Applications of materials in medicine and dentistry: orthopedic applications, , Academic Press, San Diego, CA p. 335-46; Bucholz, R., Nonallograft osteoconductive bone grafts substitutes (2002) Clin Orthop, 395, pp. 44-52; Kirker-Head, C.A., Potential applications and delivery strategies of bone morphogenetic proteins (2000) Adv Drug Deliv Rev, 43, pp. 65-92; Chen, Y., Luk, K.D.K., Cheung, K.M.C., Xu, R., Lin, M.C., Lu, W.W., Gene therapy for new bone formation using adeno-associated viral bone morphogenetic protein-2 vectors (2003) Gene Ther, 10 (16), pp. 1345-1353; Tseng, W.-C., Huang, L., Liposome-based gene therapy (1998) Res Focus, 1 (5); Leach, J.K., Mooney, D., Bone engineering by controlled delivery of osteoinductive molecules and cells (2004) Expert Opin, 4 (7); Dragoo, J.L., Choi, J.Y., Lieberman, J.R., Huang, J., Zuk, P.A., Zhang, J., Bone induction by BMP-2 transduced stem cells derived from human fat (2003) J Orthop Res, 21 (4), pp. 622-629; Eliyahu, H., Barenholz, Y., Domb, A.J., Polymers for DNA delivery (2005) Molecules, 10, pp. 34-64; Penque, D., Terapia génica: um objectivo ou uma realidade (2000) Boletim Biotecnol, 66, pp. 16-19; Winn, S.R., Hu, Y., Sfeir, C., Hollinger, J.O., Gene therapy approaches for modulating bone regeneration (2000) Adv Drug Deliv Rev, 42 (1-2), pp. 121-138; Lima, N., Mota, M., (2003) Biotecnologia, fundamentos e aplicações, , Lidel, Lisboa p. 368-73; Luo, D., Saltzman, W.M., Synthetic DNA delivery systems (2000) Nat Biotechnol, 18, pp. 33-37; Kikuchi, H., Suzuki, N., Ebihara, K., Morita, H., Ishii, Y., Kikuchi, A., Gene delivery using liposome technology (1999) J Control Release, 62 (1-2), pp. 269-277; Liu, F., Huang, L., Development of non-viral vectors for systemic gene delivery (2002) J Control Release, 78 (1-3), pp. 259-266; Girao da Cruz, M.T., Simoes, S., Pires, P.P.C., Nir, S., Pedroso de Lima, M.C., Kinetic analysis of the initial steps involved in lipoplex-cell interactions: effect of various factors that influence transfection activity (2001) Biochim Biophys Acta (BBA) - Biomembr, 1510 (1-2), pp. 136-151; Zuidam, N.J., Barenholz, Y., Electrostatic and structural properties of complexes involving plasmid DNA and cationic lipids commonly used for gene delivery (1998) Biochim Biophys Acta (BBA) - Biomembr, 1368 (1), pp. 115-128; Tros de Ilarduya, C., Arangoa, M.A., Moreno-Aliaga, M.J., Duzgunes, N., Enhanced gene delivery in vitro and in vivo by improved transferrin-lipoplexes (2002) Biochim Biophys Acta (BBA) - Biomembr, 1561 (2), pp. 209-221; Simoes, S., Pires, P., Cruz, M.T.G.d., Duzgunes, N., Pedroso de Lima, M.C., Gene delivery by cationic liposome-DNA complexes containing transferrin or serum albumin (2003) Methods Enzymol, 373, pp. 369-383; Woo-Jeong, C., Jin-Ki, K., Sung-Hee, C., Jeong-Sook, P., Woong Shick, A., Kima, C.-K., Low toxicity of cationic lipid-based emulsion for gene transfer (2004) Biomaterials, 25 (27), pp. 5893-5903; Koe, G.S., Way, H.L., Quentingco, G.M., Smith, J.G., Wedeking, T., Niven, R.W., The effect of mixing on the formation of DNA/liposome complexes (1997) Pharmacy, p. 14; Lasic, D.D., Templeton, N.S., Liposomes in gene therapy (1996) Adv Drug Deliv Rev, 20 (2-3), pp. 221-266; Pedroso de Lima, M.C., Simoes, S., Pires, P., Faneca, H., Duzgunes, N., Cationic lipid-DNA complexes in gene delivery: from biophysics to biological applications (2001) Adv Drug Deliv Rev, 47 (2-3), pp. 277-294; Hirsch-Lerner, D., Zhang, M., Eliyahu, H., Ferrari, M.E., Wheeler, C.J., Barenholz, Y., Effect of "helper lipid" on lipoplex electrostatics (2005) Biochim Biophys Acta (BBA) - Biomembr, 1714 (2), pp. 71-84; Torricelli, P., Fini, M., Giavaresi, G., Borsari, V., Carpi, A., Nicolini, A., Comparative interspecies investigation on osteoblast cultures: data on cell viability and synthetic activity (2003) Biomed Pharmacother, 57 (1), pp. 57-62; Corsi, K., Chellat, F., Yahia, L., Fernandes, J.C., Mesenchymal stem cells, MG63 and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24 (7), pp. 1255-1264; Mislick, K.A., Baldeschwieler, J.D., Evidence for role of proteoglycans in cation-mediated gene transfer (1996) Proc Natl Acad Sci USA, 93 (22), pp. 12349-12354; Duzgunes, N., Nir, S., Mechanisms and kinetics of liposome-cell interactions (1999) Adv Drug Deliv Rev, 40 (1-2), pp. 3-18; Radwan Almofti, M., Harashima, H., Shinohara, Y., Almofti, A., Baba, Y., Kiwada, H., Cationic liposome-mediated gene delivery: biophysical study and mechanism of internalization (2003) Arch Biochem Biophys, 410 (2), pp. 246-253; Simões, S., Filipe, A., Faneca, H., Mano, M., Penacho, N., Duzgunes, N., Cationic liposomes for gene delivery (2005) Expert Opin, 2 (2); Rejman, J., Bragonzi, A., Conese, M., Role of clathrin- and caveolae-mediated endocytosis in gene transfer mediated by lipo- and polyplexes (2005) Mol Ther, 12 (3), pp. 468-474
Keywords: 1,2 dioleoyl 3 trimethylammoniopropane; animal cell; Animals; article; bone cell; bone development; bone tissue; Cationic liposomes; Cell Line; cell type; complex formation; controlled study; Cytotoxicity; DNA; drug mechanism; gene expression regulation; Gene therapy; Gene transfer; genetic transfection; Genetic Vectors; human; human cell; internalization; lipoplex; liposome; Liposomes; materials testing; Mice; nonhuman; nonviral gene delivery system; osteoblast; Osteoblasts; Osteogenesis; Particle Size; plasmid; priority journal; Transfection; transferrin; Zeta potential

Cell division detection on the arabidopsis thaliana root - Marcuzzo, M.; Guichard, T.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
The study of individual plant cells and their growth structure is an important focus of research in plant genetics. To obtain development information at cellular level, researchers need to perform in vivo imaging of the specimen under study, through time-lapse confocal microscopy. Within this research field it is important to understand mechanisms like cell division and elongation of developing cells. We describe a tool to automatically search for cell division in the Arabidopsis thaliana using information of nuclei shape. The nuclei detection is based on a convergence index filter. Cell division detection is performed by an automatic classifier, trained through cross-validation. The results are further improved by a stability criterion based on the Mahalanobis distance of the shape of the nuclei through time. With this approach, we can achieve a correct detection rate of 94.7%. © 2009 Springer Berlin Heidelberg.
Conference code: 77027Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-02172-5_23Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPReferences: Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res, 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A.: Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo. In: Motion 2007, p. 13 (2007)Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation, classification, and tracking of cancer cell nuclei in time-lapse microscopy (2006) IEEE Trans. on Biomedical Engineering, 53 (4), pp. 762-766; Mao, K.Z., Zhao, P., Tan, P., Supervised learning-based cell image segmentation for p53 immunohistochemistry (2006) IEEE Trans. on Biomedical Engineering, 53 (6), pp. 1153-1163; Yang, X., Li, H., Zhou, X., Nuclei segmentation using marker-controlled watershed, tracking using mean-shift, and kalman filter in time-lapse microscopy (2006) IEEE Trans. on Circuits and Systems I-Regul. Papers, 53 (11), pp. 2405-2414; Harder, N., M-Bermudez, F., Godinez, W., Ellenberg, J., Eils, R., Rohr, K., Automated analysis of mitotic cell nuclei in 3d fluorescence microscopy image sequences (2008) Workshop on Bio-Image Informatics: Biological Imaging, Computer Vision and Data Mining; Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Trans. on Image Processing, 8 (8); Wei, J., Hagihara, Y., Kobatake, H., Detection of rounded opacities on chest radiographs using convergence index filter (1999) Proceedings of the Int. Conference on Image Analysis and Processing, pp. 757-761; Pereira, C.S., Fernandes, H., Mendonça, A.M., Campilho, A.C.: Detection of lung nodule candidates in chest radiographs. In: Martí, J., Benedí, J.M., Mendonça, A.M., Serrat, J. (eds.) IbPRIA 2007. LNCS, 4478, pp. 170-177. Springer, Heidelberg (2007)Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., A hybrid approach for cell image segmentation (2008) LNCS, 5112, pp. 739-749. , Campilho, A, Kamel, M.S, eds, ICIAR 2008, Springer, Heidelberg Sponsors: International Association for Pattern Recognition (IAPR); Fundacao para a Ciencia e a Tecnologia (FCT)
Keywords: A-stability; Arabidopsis thaliana; Automatic classifiers; Bioinformatics; Cell divisions; Cell membranes; cell proliferation; Cellular levels; confocal microscopy; Cross validation; Detection rates; Growth structures; Image analysis; In-plants; In-Vivo imaging; Mahalanobis distances; Pattern recognition; Plant cells; research; Research fields; Stability criteria

Cellular alignment induction during early in vitro culture stages using micropatterned glass coatings produced by sol-gel process - Pelaez-Vargas, A.; Ferrell, N.; Fernandes, M.H.; Hansford, D.J.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2009)
Cell behaviour such as adhesion, morphology, proliferation and functional activity are highly influenced by surface properties including hydrophobicity, roughness, texture and morphology. These surface properties may be controlled using a mixture of additive coating techniques to produce glass coatings by sol-gel process and soft lithography on dental ceramics. The purpose of this work was to compare cell adhesion and early orientation of Human Bone Marrow (HBM) cells cultured on micro-patterned (micro-PGC) and on flat glass coatings (FGC) produced by sol-gel processing. Spin coating was used to apply SiO 2 flat coatings on glass substrates as model surfaces. Photolithography was applied to produce master patterns with microscale dimensions. A moulding technique was used to print micropatterned SiO 2 glass coatings produced by a sol-gel process. The coatings were then sintered, sterilized and cultured with HBM cells derived from primary cultures, using a standardized protocol, for 1 and 7 days. Cell morphology and orientation were observed using scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). Flat and MPGC with line shaped features were produced. Cells presented a typical osteoblastic morphology on flat surfaces while slimmer, preferentially oriented and more elongated morphologies could be seen on line micro-patterned surfaces. HBM cells cultured on flat glass coatings showed increased tendency to spread and to assume more randomized proliferation when compared to the cells on the micro-patterned glass coatings. Micro-patterned glass coatings showed higher orientation control and smaller delay in the rate of proliferation, in early stages of in vitro culture as compared to flat coatings. These preliminary studies revealed that Micro-PGC induce significant morphological changes and controlled orientation of HBM cells during early stages of cell proliferation.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAEdoi: 10.4028/0-87849-353-0.303Language of Original Document: EnglishCorrespondence Address: Pelaez-Vargas, A.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do PortoPortugal; email: alejopv@ineb.up.ptReferences: Warashina, H., Sakano, S., Kitamura, S., Yamauchi, K.I., (2003) Biomaterials, 24, pp. 3655-3661;Scarano, A., Piattelli, M., Caputi, S., Favero, G.A., Piattelli, A., (2004) J Periodontol, 75, pp. 292-296; Manicone, P.F., Rossi Iommetti, P., Raffaelli, L., (2007) J Dent, 35, pp. 819-826; Covacci, V., Bruzzese, N., Maccauro, G., Andreassi, C., (1999) Biomaterials, 20, pp. 371-376; Silva, V.V., Lameiras, F.S., Lobato, Z.I., (2002) J Biomed Mater Res, 63, pp. 583-590; Oliva, J., Oliva, X., Oliva, J., (2007) Int J Oral Maxillofac Implants, 22, pp. 430-435; Klinge, B., Hultin, M., Berglundh, T., (2005) Dent Clin North Am, 49, pp. 661-676; Wennerberg, A., Albrektsson, T., Andersson, B., Krol, J.J., (1995) Clin Oral Impl Res, 6, pp. 24-30; Brunette, D.M., Kenner, G.S., Gould, T.R., (1983) J Dent Res, 62, pp. 1045-1048; Pelaez, A., Pareja, A., Garcia, C., Marquez, M., (2005) Key Eng Mater, 284, pp. 593-596; Curtis, A., Wilkinson, C., (1997) Biomaterials, 18, pp. 1573-1583; Ito, Y., (1999) Biomaterials, 20, pp. 2333-2342; Tan, J., Saltzman, W.M., (2004) Biomaterials, 25, pp. 3593-3601; Gallego, D., Ferrell, N., Sun, Y., Hansford, D.J., (2008) Mater Sci Eng C, 28, pp. 353-358; Xia, Y., Whitesides, G.M., (1998) Angew. Chem. Int. Ed, 37, pp. 550-575
Keywords: Adhesion; cell adhesion; Cell behaviours; Cell culture; Cell morphologies; cell proliferation; Cells; Coatings; Colloids; Confocal laser scanning microscopies; confocal microscopy; Contact guidance; Controlled orientations; cytology; Dental ceramics; Dental Materials; Flat glass; Flat surfaces; Functional activities; Gelation; Gels; glass; Glass ceramics; Glass coatings; Glass substrates; In-vitro; Micro-patterned; Micro-patterned surfaces; Micro-scale; Micromachining; Micropatterning; Model surfaces; Morphological changes; morphology; Nanostructured materials; Orientation controls; Primary cultures; Scanning; Scanning electron microscopy; Scanning electrons; SEM; Silicon compounds; Soft lithographies; Sol-gel; Sol-gel process; Sol-gel processing; Sol-gels; Sols; Surface Properties; Thermal spraying; Trace analysis

Chromatographic pattern recognition using optimized one-class classifiers - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
This paper presents a method for automating the selection of the rejection rate of one-class classifiers aiming at optimizing the classifier performance. These classifiers are used in a new classification approach to deal with class imbalance in Thin-Layer Chromatography (TLC) patterns, which is due to the huge difference between the number of normal and pathological cases, as a consequence of the rarity of Lysosomal Storage Disorders (LSD) diseases. The classification is performed in two decision stages, both implemented using optimized one-class classifiers: the first stage aims at recognizing most of the normal samples; the outliers of this first decision level are presented to the second stage, which is a multiclassifier prepared to deal with both pathological and normal patterns. The results that were obtained proved that the proposed methodology is able to overcome some of the difficulties associated with the choice of the rejection rate of one-class classifiers, and generally contribute to the minimization of the imbalance problem in TLC pattern classification. © 2009 Springer Berlin Heidelberg.
Conference code: 77027Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-02172-5_58Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, Porto 4200-465, Portugal; email: ats@isep.ipp.ptReferences: Skurichina, M., Raudys, S., Duin, R.P.W., K-Nearest Neighbors Directed Noise Injection in Multilayer Perceptron Training (2000) IEEE Transactions on Neural Networks, 11;Chawla, N.V., Japkowicz, N., Kolcz, A., Editorial: Special Issue: Learning from Imbal-anced Data Sets (2004) Sigkdd Explorations, 6, pp. 1-6; Tax, D.M.J., (2001) One-class Classification; Concept-learning in the Absence of Counterexamples, , Ph.D. thesis: Delft University of Technology; Durand, G., Seta, N., Protein Glycosylation and Diseases: Blood and Urinary Oligosac-charides as Markers for Diagnosis and Therapeutic Monitoring (2000) Clin. Chem, 46, pp. 795-805; Sewell, A.C., Urinary Oligosaccharides. Techniques in Diagnostic Human (1991) Biochemical Genetics, pp. 219-231; Pekalska, E., Duin, R.P.W., Dissimilarity Representations Allow for Building Good Classifiers (2002) Pattern Recogn. Lett, 23, pp. 943-956; Sousa, A.V., Mendonça, A.M., Campilho, A., Dissimilarity-based Classification of Chromatographic Profiles (2008) Pattern Analysis and Applications, 11 (3-4), pp. 409-423; Sousa, A.V., Mendonça, A.M., Campilho, A., Minimizing the Imbalance Problem in Chromatographic Profile Classification with One-class Classifiers (2008) LNCS, 5112, pp. 413-422. , Campilho, A, Kamel, M.S, eds, ICIAR 2008, Springer, Heidelberg; Sousa, A.V., Mendonça, A.M., Campilho, A., Chromatographic Pattern Classification (2008) IEEE Trans. on Biomedical Engineering, 55 (6), pp. 1687-1696; Visa, S., Ralescu, A., Learning Imbalanced and Overlapping Classes Using Fuzzy Sets (2003) Workshop on Learning from Imbalanced Datasets II, ICML, , Washington DC Sponsors: International Association for Pattern Recognition (IAPR); Fundacao para a Ciencia e a Tecnologia (FCT)
Keywords: Chromatographic analysis; Class imbalance; Classification approach; Classifier performance; Classifiers; Decision levels; Image analysis; Imbalance problem; Learning systems; Lysosomal storage disorder; Multi-classifier; One-class classifier; Optimization; Pathological case; Pattern classification; Pattern recognition; Rejection rates; Thin layer chromatography

Contextual classification of image patches with latent aspect models - Monay, F.; Quelhas, P.; Odobez, J.-M.; Gatica-Perez, D. (Eurasip Journal on Image and Video ProcessingEurasip J. Image Video Process., 2009)
We present a novel approach for contextual classification of image patches in complex visual scenes, based on the use of histograms of quantized features and probabilistic aspect models. Our approach uses context in two ways: (1) by using the fact that specific learned aspects correlate with the semantic classes, which resolves some cases of visual polysemy often present in patch-based representations, and (2) by formalizing the notion that scene context is image-specificwhat an individual patch represents depends on what the rest of the patches in the same image are. We demonstrate the validity of our approach on a man-made versus natural patch classification problem. Experiments on an image collection of complex scenes show that the proposed approach improves region discrimination, producing satisfactory results and outperforming two noncontextual methods. Furthermore, we also show that co-occurrence and traditional (Markov random field) spatial contextual information can be conveniently integrated for further improved patch classification.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusArt. No.: 602920doi: 10.1155/2009/602920Language of Original Document: EnglishCorrespondence Address: Monay, F.; Idiap Research Institute Martigny, 1920 Martigny, Switzerland; email: florent.monay@idiap.chReferences: Kumar, S., Hebert, M., Discriminative random fields: A discriminative framework for contextual interaction in classification, 2, pp. 1150-1157. , Proceedings of the IEEE International Conference on Computer Vision (ICCV 03) October 2003 Nice, France;Lazebnik, S., Schmid, C., Ponce, J., Affine-invariant local descriptors and neighborhood statistics for texture recognition, 1, pp. 649-655. , Proceedings of the IEEE International Conference on Computer Vision (ICCV 03) October 2003 Nice, France; Vogel, J., Schiele, B., Natural scene retrieval based on a semantic modeling step, 3115, pp. 207-215. , Proceedings of the 3rd International Conference on Image and Video Retrieval (CIVR 04) July 2004 Dublin, Ireland Lecture Notes in Computer Science; Shotton, J., Winn, J., Rother, C., Criminisi, A., TextonBoost: Joint appearance, shape and context modeling for multi-class object recognition and segmentation, 3951, pp. 1-15. , Proceedings of the 9th European Conference on Computer Vision (ECCV 06) May 2006 Graz, Austria Lecture Notes in Computer Science; Lowe, D.G., Distinctive image features from scale-invariant keypoints (2004) International Journal of Computer Vision, 60 (2), pp. 91-110; Dorko, G., Schmid, C., Selection of scale-invariant parts for object class recognition, 1, pp. 634-640. , Proceedings of the 9th IEEE International Conference on Computer Vision (ICCV 03) October 2003 Nice, France; Fei-Fei, L., Perona, P., A Bayesian hierarchical model for learning natural scene categories, 2, pp. 524-531. , Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR 05) June 2005 San Diego, Calif, USA; Quelhas, P., Monay, F., Odobez, J.-M., Gatica-Perez, D., Tuytelaars, T., Van Gool, L., Modeling scenes with local descriptors and latent aspects, 1, pp. 883-890. , Proceedings of the IEEE International Conference on Computer Vision (ICCV 05) October 2005 Beijing, China; Sivic, J., Russell, B.C., Efros, A.A., Zisserman, A., Freeman, W.T., Discovering object categories in image collections, , Proceedings of the 10th IEEE International Conference on Computer Vision (ICCV 05) October 2005 Beijing, China; Li, S.Z., (1995) Markov Random Field Modeling in Computer Vision, , New York, NY, USA Springer; Kumar, S., Hebert, M., Man-made structure detection in natural images using a causal multiscale random field, 1, pp. 119-126. , Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR 03) June 2003 Madison, Wis, USA; Murphy, K., Torralba, A., Freeman, W., Using the forest to see the trees: A graphical model relating features, objects and scenes, , Proceedings of the Neural Information Processing Systems December 2003 Vancouver, Canada; Geman, S., Geman, D., Stochastic relaxation, Gibbs distributions, and the Bayesian restoration of images (1984) IEEE Transactions on Pattern Analysis and Machine Intelligence, 6 (6), pp. 721-741; Quelhas, P., Monay, F., Odobez, J.-M., Gatica-Perez, D., Tuytelaars, T., A thousand words in a scene (2007) IEEE Transactions on Pattern Analysis and Machine Intelligence, 29 (9), pp. 1575-1589; Quelhas, P., Odobez, J.-M., Multi-level local descriptor quantization for bag-of-visterms image representation, pp. 242-249. , Proceedings of the 6th ACM International Conference on Image and Video Retrieval (CIVR 07) July 2007 Amsterdam, The Netherlands; Csurka, G., Dance, C., Fan, L., Willamowski, J., Bray, C., Visual categorization with bags of keypoints, pp. 59-74. , Proceedings of the European Conference on Computer Vision (ECCV 04) May 2004 Prague, Czech Republic; Marszaek, M., Schmid, C., Spatial weighting for bag-of-features, 2, pp. 2118-2125. , Proceedings of IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR 06) June 2006 New York, NY, USA; Wang, G., Zhang, Y., Fei-Fei, L., Using dependent regions for object categorization in a generative framework, 2, pp. 1597-1604. , Proceedings of IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR 06) June 2006 New York, NY, USA; Sivic, J., Zisserman, A., Video Google: A text retrieval approach to object matching in videos, 2, pp. 1470-1477. , Proceedings of the 9th IEEE International Conference on Computer Vision (ICCV 03) October 2003 Nice, France; Willamowski, J., Arregui, D., Csurka, G., Dance, C.R., Fan, L., Categorizing nine visual classes using local appearance descriptors, , Proceedings of the Workshop on Learning for Adaptable Visual Systems (LAVS), in Conjunction with the International Conference on Pattern Recognition (ICPR 04) August 2004 Cambridge, UK; Bosch, A., Zisserman, A., Muoz, X., Scene classification via pLSA, 3954, pp. 517-530. , Proceedings of the 9th European Conference on Computer Vision (ECCV 06) May 2006 Graz, Austria Lecture Notes in Computer Science; Hofmann, T., Unsupervised learning by probabilistic latent semantic analysis (2001) Machine Learning, 42 (12), pp. 177-196; Blei, D.M., Ng, A.Y., Jordan, M.I., Latent Dirichlet allocation (2003) Journal of Machine Learning Research, 3 (45), pp. 993-1022; Pal, N.R., Pal, S.K., A review on image segmentation techniques (1993) Pattern Recognition, 26 (9), pp. 1277-1294; Carson, C., Thomas, M., Belongie, S., Hellerstein, J.M., Malik, J., Blob-world: A system for region-based image indexing and retrieval, pp. 509-516. , Proceedings of the 3rd International Conference on Visual Information Systems (VISUAL 99) June 1999 Amsterdam, The Netherlands Springer; Duygulu, P., Barnard, K., De Freitas, J.F.G., Forsyth, D.A., Object recognition as machine translation: Learning a lexicon for a fixed image vocabulary, 2353, pp. 97-112. , Proceedings of the 7th European Conference on Computer Vision (ECCV 02) May 2002 Copenhagen, Denmark Lecture Notes in Computer Science; Vogel, J., Schiele, B., A semantic typicality measure for natural scene categorization, 3175, pp. 195-203. , Proceedings of the 26th DAGM Pattern Recognition Symposium August-September 2004 Tbingen, Germany Lecture Notes in Computer Science; Verbeek, J.J., Triggs, B., Region classification with Markov field aspect models, pp. 1-8. , Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR 07) June 2007 Minneapolis, Minn, USA; Shi, J., Malik, J., Normalized cuts and image segmentation, pp. 731-737. , Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR 97) June 1997 San Juan, Puerto Rico, USA; Kumar, M.P., Torr, P.H.S., Zisserman, A., Obj cut, 1, pp. 18-25. , Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR 05) June 2005 San Diego, Calif, USA; Leibe, B., Leonardis, A., Schiele, B., Combined object categorization and segmentation with an implicit shape model, pp. 17-32. , Proceedings of the 8th European Conference on Computer Vision (ECCV 04) May 2004 Prague, Czech Republic; Russell, B.C., Freeman, W.T., Efros, A.A., Sivic, J., Zisserman, A., Using multiple segmentations to discover objects and their extent in image collections, 2, pp. 1605-1612. , Proceedings of IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR 06) June 2006 New York, NY, USA; Monay, F., Quelhas, P., Odobez, J.-M., Gatica-Perez, D., Integrating co-occurrence and spatial contexts on patch-based scene segmentation, p. 14. , Proceedings of the IEEE Conference on Computer Vision and Pattern Recognition Workshop (CVPR 06) June 2006 New York, NY, USA; Cao, L., Fei-Fei, L., Spatially coherent latent topic model for concurrent object segmentation and classification, , Proceedings of the 11th IEEE International Conference on Computer Vision (ICCV 07) October 2007 Rio de Janeiro, Brazil; Liu, D., Chen, T., Background cutout with automatic object discovery, 4, pp. 345-348. , Proceedings of IEEE International Conference on Image Processing (ICIP 07) September 2007 San Antonio, Tex, USA; Tuytelaars, T., Van Gool, L., Content-based image retrieval based on local affinely invariant regions, 1614, pp. 493-500. , Proceedings of the 3rd International Conference on Visual Information and Information Systems June 1999 Amsterdam, The Netherlands Lecture Notes in Computer Science; Mikolajczyk, K., Schmid, C., A performance evaluation of local descriptors, 2, pp. 257-263. , Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR 03) June 2003 Madison, Wis, USA; Mikolajczyk, K., Tuytelaars, T., Schmid, C., A comparison of affine region detectors (2005) International Journal of Computer Vision, 65 (12), pp. 43-72; Baeza-Yates, R., Ribeiro-Neto, B., (1999) Modern Information Retrieval, , New York, NY, USA ACM Press; Monay, F., Quelhas, P., Gatica-Perez, D., Odobez, J.-M., Constructing visual models with a latent space approach, 3940, pp. 115-126. , Proceedings of the Subspace, Latent Structure and Feature Selection, Statistical and Optimization, Perspectives Workshop (SLSFS 05) February 2006 Bohinj, Slovenia Lecture Notes in Computer Science; Fergus, R., Fei-Fei, L., Perona, P., Zisserman, A., Learning object categories from Googles image search, 2, pp. 1816-1823. , Proceedings of the 10th IEEE International Conference on Computer Vision (ICCV 05) October 2005 Beijing, China; Buntine, W.L., Variational extensions to em and multinomial PCA, 2430, pp. 23-34. , Proceedings of the 13th European Conference on Machine Learning August 2002 Helsinki, Finland Lecture Notes in Computer Science; Bishop, C., (1995) Neural Networks for Pattern Recognition, , Oxford, UK Oxford University

Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology - Zijlmans, M.; Sá-Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in HealthcareSimul. Healthc., 2009)
We identified errors in the software implementation of the mathematical model presented in: Sá Couto CD, van Meurs WL, Goodwin JA, Andriessen P. A model for educational simulation of neonatal cardiovascular pathophysiology. Simul Healthcare 2006;1:4-12. Simulation results obtained with corrected code are presented for future reference. All but one of the simulation results do not differ by more than 9% from the previously published results. The heart rate response to acute loss of 30% of blood volume, simulated with corrected code is stronger than published target data. This modeling error was masked by errors in code implementation. We improved this response and the model by adjusting the gains and adding thresholds and saturations in the baroreflex model. General considerations on identification of model and code errors and model validity are presented. Copyright © 2009 Society for Simulation in Healthcare.
Cited By (since 1996): 4Export Date: 21 November 2012Source: Scopusdoi: 10.1097/SIH.0b013e31818b27a8Language of Original Document: EnglishCorrespondence Address: Zijlmans, M.; INEB-Instituto de Engenharia Biomédica, Porto, PortugalReferences: Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-12;Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E.W., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Beneken, J.E.W., A mathematical approach to cardiovascular function (1965) The Uncontrolled Human System, , Thesis, University of Utrecht, The Netherlands; Andriessen, P., Bambang Oetomo, S., Peters, C., Vermeulen, B., Wijn, P.F.F., Blanco, C.E., Baroreceptor reflex sensitivity in human neonates: The effect of postmenstrual age (2005) J Physiol, 568, pp. 333-341; Segar, J.L., Roghair, R.D., Segar, E.M., Bailey, M.C., Scholz, T.D., Lamb, F.S., Early gestation dexamethasone alters baroreflex and vascular responses in newborn lambs before hypertension (2006) Am J Physiol Regul Integr Comp Physiol, 291, pp. R481-R488; Wallgren, G., Barr, M., Rudhe, U., Hemodynamic studies of induced acute hypo- and hypervolemia in the newborn infant (1964) Acta Paediatr, 53, pp. 1-12
Keywords: aorta coarctation; article; Baroreflex; bleeding; blood pressure; blood volume; Cardiac Output; cardiovascular disease; Cardiovascular Diseases; Cardiovascular physiology; computer program; Computer simulation; Congenital heart defect; congenital heart malformation; diastolic blood pressure; Education, Medical; Erratum; Fallot tetralogy; great vessels transposition; heart output; Heart rate; heart right ventricle pressure; human; Humans; Infant, Newborn; lung pressure; mathematical model; mean arterial pressure; medical education; medical error; methodology; Neonate; Neonatology; newborn; patent ductus arteriosus; pathophysiology; physiology; pressoreceptor reflex; priority journal; simulation; Software Design; systolic blood pressure; Validation; validity; vascular resistance; Verification; vital sign

The correlation between the adsorption of adhesive proteins and cell behaviour on hydroxyl-methyl mixed self-assembled monolayers - Barrias, C.C.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A.; Granja, P.L. (BiomaterialsBiomaterials, 2009)
The objective of this study was to compare the biological effects of two key cell-adhesive proteins, fibronectin (FN) and vitronectin (VN), upon adsorption onto molecularly-designed model surfaces. Single-component and mixed self-assembled monolayers (SAMs) of alkanethiols on gold with OH and CH 3 terminal groups were prepared at 100%, 65%, 36% and 0% of OH at the surface, to generate a range of surfaces with a simple chemistry and a wettability gradient. FN and VN were adsorbed under non-competitive (single-protein solutions) and competitive (multi-protein solutions) conditions, and compared at different levels: adsorbed amount (radiolabelling), elution, functional presentation of cell-binding domains (ELISA), and role in mediating cell adhesion (antibody-based assay). The observed trends were related to mesenchymal stem cell response in terms of adhesion and overall cell morphology. Under non-competitive conditions, adsorption of both proteins increased with surface hydrophobicity. The presence of competitive proteins significantly decreased the adsorbed amounts, although both proteins were still detected in all SAMs. Adsorption of FN followed a trend similar to that of non-competitive conditions, while adsorption of VN was higher on 100%OH-SAMs. Concerning elution, retention of adsorbed VN was always higher than that of FN. For both proteins, functional presentation of cell-binding domains was more effective on the more hydrophilic 100%OH-SAMs. This fact, coupled to the ability of this type of SAMs to selectively recruit and retain VN in the presence of competitive serum proteins, seems to correlate with the better cell response observed on these surfaces, as compared with hydrophobic 0%OH(100%CH 3)-SAMs. © 2008 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2008.09.048PubMed ID: 18952279Language of Original Document: EnglishCorrespondence Address: Barrias, C.C.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, R. Campo Alegre 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: fibronectin, 86088-83-7; gold, 7440-57-5; thiol derivative, 13940-21-1; Biocompatible Materials; Fibronectins; VitronectinReferences: Wilson, C.J., Clegg, R.E., Leavesley, D.I., Pearcy, M.J., Mediation of biomaterial-cell interactions by adsorbed proteins: a review (2005) Tissue Eng, 11, pp. 1-18;García, A.J., Vega, M.D., Boettiger, D., Modulation of cell proliferation and differentiation through substrate-dependent changes in fibronectin conformation (1999) Mol Biol Cell, 10, pp. 785-798; Keselowsky, B.G., Collard, D.M., García, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res A, 66, pp. 247-259; Underwood, P.A., Bennett, F.A., A comparison of the biological activities of the cell-adhesive proteins vitronectin and fibronectin (1989) J Cell Sci, 93, pp. 641-649; Steele, J.G., Johnson, G., Underwood, P.A., Role of serum vitronectin and fibronectin in adhesion of fibroblasts following seeding onto tissue culture polystyrene (1992) J Biomed Mater Res, 26, pp. 861-884; Steele, J.G., Dalton, B.A., Johnson, G., Underwood, P.A., Polystyrene chemistry affects vitronectin activity: an explanation for cell attachment to tissue culture polystyrene but not to unmodified polystyrene (1993) J Biomed Mater Res, 27, pp. 927-940; Underwood, P.A., Steele, J.G., Dalton, B.A., Effects of polystyrene surface chemistry on the biological activity of solid phase fibronectin and vitronectin, analysed with monoclonal antibodies (1993) J Cell Sci, 104, pp. 793-803; Suzuki, S., Oldberg, A., Hayman, E.G., Pierschbacher, M.D., Ruoslahti, E., Complete amino acid sequence of human vitronectin deduced from cDNA. Similarity of cell attachment sites in vitronectin and fibronectin (1985) EMBO J, 4, pp. 2519-2524; Lee, M.H., Ducheyne, P., Lynch, L., Boettiger, D., Composto, R.J., Effect of biomaterial surface properties on fibronectin-alpha5beta1 integrin interaction and cellular attachment (2006) Biomaterials, 27, pp. 1907-1916; Grinnell, F., Feld, M.K., Fibronectin adsorption on hydrophilic and hydrophobic surfaces detected by antibody binding and analyzed during cell adhesion in serum-containing medium (1982) J Biol Chem, 257, pp. 4888-4893; Sousa, S.R., Lamghari, M., Sampaio, P., Moradas-Ferreira, P., Barbosa, M.A., Osteoblast adhesion and morphology on TiO 2 depends on the competitive preadsorption of albumin and fibronectin (2008) J Biomed Mater Res A, 84, pp. 281-290; Fabrizius-Homan, D.J., Cooper, S.L., Competitive adsorption of vitronectin with albumin, fibrinogen, and fibronectin on polymeric biomaterials (1991) J Biomed Mater Res, 25, pp. 953-971; Bale, M.D., Wohlfahrt, L.A., Mosher, D.F., Tomasini, B., Sutton, R.C., Identification of vitronectin as a major plasma protein adsorbed on polymer surfaces of different copolymer composition (1989) Blood, 74, pp. 2698-2706; Thomas, C.H., McFarland, C.D., Jenkins, M.L., Rezania, A., Steele, J.G., Healy, K.E., The role of vitronectin in the attachment and spatial distribution of bone-derived cells on materials with patterned surface chemistry (1997) J Biomed Mater Res, 37, pp. 81-93; McFarland, C.D., Thomas, C.H., DeFilippis, C., Steele, J.G., Healy, K.E., Protein adsorption and cell attachment to patterned surfaces (2000) J Biomed Mater Res, 49, pp. 200-210; Love, J.C., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers to understand the interactions of man-made surfaces with proteins and cells (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-78; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Faucheux, N., Schweiss, R., Lützow, K., Werner, C., Groth, T., Self-assembled monolayers with different terminating groups as model substrates for cell adhesion studies (2004) Biomaterials, 25, pp. 2721-2730; Bernards, M.T., Jiang, S., pH-induced conformation changes of adsorbed vitronectin maximize its bovine aortic endothelial cell binding ability (2008) J Biomed Mater Res A; Martins, M.C., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67, pp. 158-171; Rodrigues, S.N., Gonçalves, I.C., Martins, M.C., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Chamberlain, J., Yamagami, T., Colletti, E., Theise, N.D., Desai, J., Frias, A., Efficient generation of human hepatocytes by the intrahepatic delivery of clonal human mesenchymal stem cells in fetal sheep (2007) Hepatology, 46, pp. 1935-1945; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, pp. 183-214. , Williams D.F. (Ed), CRC Press Inc., Harcover; Arima, Y., Iwata, H., Effect of wettability and surface functional groups on protein adsorption and cell adhesion using well-defined mixed self-assembled monolayers (2007) Biomaterials, 28, pp. 3074-3082; Capadona, J.R., Collard, D.M., Garcia, A.J., Fibronectin adsorption and cell adhesion to mixed monolayers of tri(ethylene glycol)- and methyl-terminated alkanethiols (2003) Langmuir, 19, pp. 1847-1852; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (2000) J Biomed Mater Res, 49, pp. 435-447; Wertz, C.F., Santore, M.M., Fibrinogen adsorption on hydrophilic and hydrophobic surfaces: geometrical and energetic aspects of interfacial relaxations (2002) Langmuir, 18, pp. 706-715; Pitt, W.G., Fabrizius-Homan, D.J., Mosher, D.F., Cooper, S.L., Vitronectin adsorption on polystyrene and oxidized polystyrene (1989) J Colloid Interface Sci, 129, pp. 231-239; Seiffert, D., Smith, J.W., The cell adhesion domain in plasma vitronectin is cryptic (1997) J Biol Chem, 272, pp. 13705-13710
Keywords: Adhesion; Adhesiveness; Adsorption; alkane; Animals; article; Biocompatible Materials; Biological Assay; bone marrow; Cattle; cell adhesion; Cell culture; Cell Movement; Cells; Cells, Cultured; cytology; cytoskeleton; Electric currents; Electron energy levels; enzyme linked immunosorbent assay; Fibronectin; Fibronectins; Focal adhesions; Functional groups; Functionalization; gold; human; human cell; Humans; hydrophilicity; hydrophobicity; Hydroxylation; isotope labeling; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Confocal; Missile bases; Molecular interactions; monoclonal antibody; priority journal; Protein adsorption; protein analysis; protein binding; Protein Structure, Tertiary; Proteins; Self assembled monolayers; Self-assembled monolayers; stem cell; Stem cells; Surface Properties; thiol derivative; Vitronectin

Cytotoxicity evaluation of nanocrystalline diamond coatings by fibroblast cell cultures - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
The cytotoxicity profile of nanocrystalline diamond (NCD) coatings on a Si 3N 4 ceramic was investigated. This material is envisaged to have biomedical dental applications such as burrs and surgical instruments. Two fibroblast cell culture systems were used to address the cytotoxicity of NCD-coated samples: L929 cells (a mouse permanent cell line) and human gingival fibroblasts. Cell behavior was evaluated in terms of cell adhesion, cell viability/proliferation (mitochondrial function, MTT assay) and the pattern of cell growth. Fibroblast cell behavior on standard polystyrene culture plates was used as control, as Si 3N 4 substrates have previously been shown to be biocompatible. NCD coatings provided a suitable surface for cell attachment, spreading and proliferation. Human gingival cells showed a homogeneous cytoplasm spreading, a flattened elongated morphology and a typical parallel alignment on confluent cultures. In comparison, L929 cells denoted a lower cytoplasm expansion, a heterogeneous spreading but a higher proliferation rate. For both cells, after few days, the NCD coating was completely covered with continuous cell layers. As compared to standard polystyrene culture plates, no deleterious or cytotoxic responses were observed with L929 and human fibroblast cell cultures, and in both a slight enhancement in cell proliferation was observed. In addition, the seeded NCD film allowed reproduction of the typical features of the two cell culture systems tested, further suggesting the lack of cytotoxicity of this coating. © 2008 Acta Materialia Inc.
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.08.015PubMed ID: 18819854Language of Original Document: EnglishCorrespondence Address: Amaral, M.; CICECO, Department of Ceramics and Glass Engineering, University of Aveiro, 3810-193 Aveiro, Portugal; email: margarida.amaral@ua.ptChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; diamond, 7782-40-3; polystyrene, 9003-53-6; silicon nitride, 12033-89-5; Culture Media; Diamond, 7782-40-3References: Griffin, J., Ray, P.C., Role of inert gas in the low-temperature nano-diamond chemical vapour deposition process (2006) Nanotechnology, 17, pp. 1225-1229;Mitura, S., Mitura, K., Niedzielski, P., Louda, P., Danilenko, V., Nanocrystalline diamond, its synthesis, properties and applications (2006) J Achievements Mater Manuf Eng, 16, pp. 9-16; Okrój, W., Kamińska, M., Klimek, L., Szymański, W., Walkowiak, B., Blood platelets in contact with nanocrystalline diamond surfaces (2006) Diamond Relat Mater, 15, pp. 1535-1539; Xiao, X., Wang, J., Liu, C., Carlisle, J.A., Mech, B., Greenberg, R., In vitro and in vivo evaluation of ultrananocrystalline diamond for coating of implantable retinal microchips (2006) J Biomed Mater Res B: Appl Biomater, 77 B, pp. 273-281; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour-deposited diamond (1995) Biomaterials, 16, pp. 483-488; Steinmueller-Nethl, D., Kloss, F.R., Haq, M.N.U., Rainer, M., Larsson, K., Linsmeier, C., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27, pp. 4547-4556; Wenmackers, S., Christiaens, P., Daenen, M., Haenen, K., Nesládek, M., Ven, M., DNA attachment to nanocrystalline diamond films (2005) Phys Status Solidi, 202, pp. 2212-2216; Retama, J.R., Hernando, J., Lopez-Ruiz, B., Härtl, A., Steinmüller, D., Stutzmann, M., Synthetic nanocrystalline diamond as a third-generation biosensor support (2006) Langmuir, 22, pp. 5837-5842; Siew, P.S., Loh, K.P., Poh, W.C., Zhang, H., Biosensing properties of nanocrystalline diamond film grown on polycrystalline diamond electrodes (2005) Diamond Relat Mater, 14, pp. 426-431; Jakubowski, W., Bartosz, G., Niedzielski, P., Szymanski, W., Walkowiak, B., Nanocrystalline diamond surface is resistant to bacterial colonization (2004) Diamond Relat Mater, 13, pp. 1761-1763; Trava-Airoldi, V.J., Corat, E.J., Leite, N.F., Nono, M., Ferreira, N.G., Baranauskas, V., CVD diamond burrs-development and applications (1996) Diamond Relat Mater, 5, pp. 857-860; Amar, M., Ahmed, W., Sein, H., Jones, A.N., Rego, C., Chemical vapour deposition of diamond coatings onto molybdenum dental tools (2003) J Phys Condens Matter, 15, pp. S2977-S2982; Tetsumura, A., Honda, E., Sasaki, T., Kino, K., Metallic residues as a source of artifacts in magnetic resonance imaging of the temporomandibular joint (1999) Dentomaxillofac Radiol, 28, pp. 186-190; Carvalho, C.A., Fagundes, T.C., Barata, T.E., Trava-Airoldi, V.J., Navarro, M.L., The use of CVD diamond burrs for ultraconservative cavity preparations: a report of two cases (2007) J Esthet Restor Dent, 19, pp. 19-29; Mitura, K., Niedzielski, P., Grzegorz, B., Moll, J., Walkowiak, B., Pawlowska, Z., Interactions between carbon coatings and tissue (2006) Surf Coat Technol, 201, pp. 2117-2123; Fries, M.D., Vohra, Y.K., Microcrystalline and nanocrystalline diamond film deposition on cobalt chrome alloy (1999) Thin films-stresses and mechanical properties VIII, , Vinci R., Kraft O., Moody N., Besser P., and Shaffer II E. (Eds), MRS Publications, Boston, MA; Fries, M.D., Vohra, Y.K., Properties of nanocrystalline thin films grown by MPCVD for biomedical implant purposes (2004) Diamond Relat Mater, 13, pp. 1740-1743; Papo, M.J., Catledge, S.A., Vohra, Y.K., Mechanical wear behavior of nanocrystalline and multilayer diamond coatings on temporomandibular joint implants (2004) J Mater Sci: Mater Med, 15, pp. 773-777; Sun, F.H., Zhang, Z.M., Ma, Y.P., Chen, M., Synthesis of nanocrystalline diamond films on smooth WC-Co cemented carbide substrates (2007) Int J Abrasive Technol, 1, pp. 161-172; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond Relat Mater, 12, pp. 733-737; Petzow, G., Herrmann, M., Silicon nitride ceramics (2002) Struct Bond, 102, pp. 47-167; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23, pp. 4897-4906; Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494, pp. 92-97; Chong, K.F., Loh, K.P., Vedula, S.R., Lim, C.T., Sternschulte, H., Steinmüller, D., Cell adhesion properties on photochemically functionalized diamond (2007) Langmuir, 23, pp. 5615-5621; Bajaj, P., Akin, D., Gupta, A., Sherman, D., Shi, B., Auciello, O., Ultra-nanocrystalline diamond film as an optimal cell interface for biomedical applications (2007) Biomed Microdevices, , [Epub ahead of print]; Arnold, L.F., Baram, B., In vitro culture of periodontal ligament cells (1972) J Dent Res, 51, pp. 953-959; Piche, J.E., Carnes Jr., D.L., Graves, D.T., Initial characterization of cells derived from human periodontia (1989) J Dent Res, 68, pp. 761-767; Trigo Cabral, C., Costa, M.A., Fernandes, M.H., In vitro models of periodontal cells: a comparative study of long-term gingival, periodontal ligament and alveolar bone cell cultures in the presence of β-glycerophosphate and dexamethasone (2007) J Mater Sci: Mater Med, 18, pp. 1079-1088; Bajpai, P.K., Billote, W.G., Ceramic biomaterials (1995) The biomedical engineering handbook, pp. 552-580. , Bronzino J.D. (Ed), CRC Press, Boca Raton, FL; Nishitani-Gamo, M., Ando, T., Watanabe, K., Sekita, M., Dennig, P.A., Yamamoto, K., Interfacial structures of oriented diamond on Si (1 0 0) characterized by confocal Raman spectroscopy (1997) Diamond Relat Mater, 6, pp. 1036-1040; Ferrari, A.C., Robertson, J., Origin of the 1150 cm -1 Raman mode in nanocrystalline diamond (2001) Phys Rev B, 63, pp. 121405-1-121405-4; Pfeiffer, R., Kuzmany, H., Knoll, P., Bokova, S., Salk, N., Günther, B., Evidence for trans-polyacetylene in nano-crystalline diamond films (2003) Diamond Relat Mater, 12, pp. 268-271; Zimmermann, T., Janischowsky, K., Denisenko, A., Guillén, F.J.H., Kubovic, M., Gruen, D.M., Nanocrystalline diamond pn-structure grown by hot-filament CVD (2006) Diamond Relat Mater, 15, pp. 203-206; Krauss, A.R., Auciello, O., Gruen, D.M., Jayatissa, A., Sumant, A., Tucek, J., Ultrananocrystalline diamond thin films for MEMS and moving mechanical assembly devices (2001) Diamond Relat Mater, 10, pp. 1952-1961; Amaral, M., Fernandes, A.J.S., Vila, M., Oliveira, F.J., Silva, R.F., Growth rate improvements in the hot-filament CVD deposition of nanocrystalline diamond (2006) Diamond Relat Mater, 15, pp. 1822-1827; Alberts, B., Johnson, A., Lewis, J., Raff, M., Roberts, K., Walter, P., The cytoskeleton (2002) Molecular biology of the cell. 4th ed., pp. 907-972. , Alberts B., Johnson A., Lewis J., Raff M., Roberts K., and Walter P. (Eds), Garland Publishing, New York; Stamenovic, D., Effects of cytoskeletal prestress on cell rheological behaviour (2005) Acta Biomater, 1, pp. 255-262; Freshney, T.I., Biology of cultured cells (2000) Culture of animal cells. A manual of basic technique, pp. 9-18. , Wiley-Liss, New York; Garguilo, J.M., Davis, B.A., Buddie, M., Köck, F.A.M., Nemanich, R.J., Fibrinogen adsorption onto microwave plasma chemical vapor deposited diamond films (2004) Diamond Relat Mater, 13, pp. 595-599; Ariano, P., Baldellia, P., Carbonea, E., Gilardino, A., Giudicea, A.L., Lovisolo, D., Cellular adhesion and neuronal excitability on functionalised diamond surfaces (2005) Diamond Relat Mater, 14, pp. 669-674; Heinrich, G., Grijgler, T., Rosiwal, S.M., Singer, R.F., CVD diamond coated titanium alloys for biomedical and aerospace applications (1997) Surf Coat Technol, 94-95, pp. 514-520; Müller, R., Adamschik, M., Steidl, D., Kohn, E., Thamasett, S., Stiller, S., Application of CVD-diamond for catheter ablation in the heart (2004) Diamond Relat Mater, 13, pp. 1080-1083; Nordsletten, L., Hogasen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: in vitro studies of new prosthesis coatings (1996) Biomaterials, 17, pp. 1521-1527; Aspenberg, P., Antilla, A., Konttinen, Y.T., Lappalainen, R., Goodman, S.B., Nordsletten, L., Benign response to particles of diamond and SiC: bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17, pp. 807-812; Specht, C.G., Williams, O.A., Jackman, R.B., Schoepfer, R., Ordered growth of neurons on diamond (2004) Biomaterials, 25, pp. 4073-4078; Schrand, A.M., Huang, H., Carlson, C., Schlager, J.J., Omacr Sawa, E., Hussain, S.M., Are diamond nanoparticles cytotoxic? (2007) J Phys Chem B, 111, pp. 2-7; International Organization for Standardization, ISO 10993-5: biological evaluation of medical devices. Part 5. Tests for cytotoxicity: in vitro methods. Geneva; 1992International Organization for Standardization, ISO 7405: dentistry-preclinical evaluation of biocompatibility of medical devices used in dentistry-test methods for dental materials. Geneva; 1997Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Form and function of bone (1994) Orthopedic basic science, pp. 127-185. , Simon S.P. (Ed), American Academy of Orthopedic Surgeons, Columbus, OH; Webster, T.J., Proteins: structure and interactions patterns to solid surfaces (2004) Encyclopedia of nanoscience and nanotechnology, pp. 3079-3095. , Schwarz J.A., Contescu C., and Putyera K. (Eds), Marcel Dekker, New York; Webster, T.J., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) J Biomed Mater Res, 51, pp. 475-483; Shane, A.C., Marc, D.F., Yogesh, K.V., William, R.L., Jack, E.L., Shanna, W., Nanostructured ceramics for biomedical implants (2002) J Nanosci Nanotechnol, 2, pp. 1-20; Price, R.L., Haberstroh, K.M., Webster, T.J., Enhanced functions of osteoblasts on nanostructured surfaces of carbon and alumina (2003) Med Biol Eng Comput, 41, pp. 372-375; Webster, T.J., Siegel, R.W., Bizios, R., Osteoblast adhesion on nanophase ceramics (1999) Biomaterials, 20, pp. 1221-1227; Perla, V., Webster, T.J., Better osteoblast adhesion on nanoparticulate selenium-A promising orthopedic implant material (2005) J Biomed Mater Res, 75 A, pp. 356-364
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; animal cell; Animals; article; Biocompatibility; Biomedical dental applications; biomedicine; cell adhesion; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell spreading; cell structure; cell surface; cell survival; cell viability; ceramics; controlled study; Culture Media; cytoplasm; Cytotoxicity; dentistry; diamond; Fibroblast cell cultures; fibroblast culture; Fibroblasts; gingiva; human; human cell; Humans; material coating; Mice; Microscopy, Electron, Scanning; mitochondrial respiration; mouse; nanocrystal; Nanocrystalline diamond coating; Nanostructures; nonhuman; polystyrene; priority journal; Silicon nitride; Surgical instrument

Decision trees using the minimum Entropy-of-error principle - De Sá, J.P.M.; Gama, J.; Sebastião, R.; Alexandre, L.A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
Binary decision trees based on univariate splits have traditionally employed so-called impurity functions as a means of searching for the best node splits. Such functions use estimates of the class distributions. In the present paper we introduce a new concept to binary tree design: instead of working with the class distributions of the data we work directly with the distribution of the errors originated by the node splits. Concretely, we search for the best splits using a minimum entropy-of-error (MEE) strategy. This strategy has recently been applied in other areas (e.g. regression, clustering, blind source separation, neural network training) with success. We show that MEE trees are capable of producing good results with often simpler trees, have interesting generalization properties and in the many experiments we have performed they could be used without pruning. © 2009 Springer Berlin Heidelberg.
Conference code: 77256Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-03767-2_97Language of Original Document: EnglishCorrespondence Address: De Sá, J. P. M.; INEB-Instituto de Engenharia Biomédica, Porto, Portugal; email: jmsa@fe.up.ptReferences: Asuncion, A., Newman, D.J., (2007) UCI Machine Learning Repository, , http://www.ics.uci.edu/̃mlearn/MLRepository.html, Univ. of California, SICS, Irvine, CA;Breiman, L., Friedman, J.H., Olshen, R.A., Stone, C.J., (1993) Classification and Regression Trees, , Chapman & Hall/CRC, Boca Raton; Devroye, L., Giörfi, L., Lugosi, G., (1996) A Probabilistic Theory of Pattern Recognition, , Springer, Heidelberg; Forina, M., Armanino, C., Eigenvector Projection and Simplified Nonlinear Mapping of Fatty Acid Content of Italian Olive Oils (1981) Ann. Chim, 72, pp. 127-155; Loh, W.-Y., Shih, Y.-S., Split Selection Methods for Classification Trees (1997) Statistica Sinica, 7, pp. 815-840; Marques de Sá, J.P., (2007) Applied Statistics Using SPSS, STATISTICA, MATLAB and R, , 2nd edn. Springer, Heidelberg; Quinlan, J.R., Induction of Decision Trees (1986) Machine Learning, 1, pp. 81-106; Quinlan, J.R.: C4.5 Programs for Machine Learning. Morgan Kaufmann, San Francisco (1993)Silva, L.M., Felgueiras, C.S., Alexandre, L.A., Marques de Sá, J., Error Entropy in Classification Problems: A Univariate Data Analysis (2006) Neural Comp, 18, pp. 2036-2061; Silva, L.M., Embrechts, M.J., Santos, J.M., de Sá, J.M., The influence of the risk functional in data classification with mLPs (2008) LNCS, 5163, pp. 185-194. , Kůrková, V, Neruda, R, Koutník, J, eds, ICANN 2008, Part I, Springer, Heidelberg Sponsors: University of Munster; International Association for Pattern Recognition; Olympus Soft Imaging Solutions GmbH; Philips
Keywords: Binary decision trees; Binary trees; Blind source separation; Class distributions; decision trees; Electronic medical equipment; entropy; entropy-of-error; Generalization properties; Image analysis; Minimum entropy; Neural network training; Neural networks; New concept; node split criteria; Univariate

The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect - Grellier, M.; Granja, P.L.; Fricain, J.-C.; Bidarra, S.J.; Renard, M.; Bareille, R.; Bourget, C.; Amédée, J.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Bone regeneration seems to be dependant on cell communication between osteogenic and endothelial cells arising from surrounding blood vessels. This study aims to determine whether endothelial cells can regulate the osteogenic potential of osteoprogenitor cells in vitro and in vivo, in a long bone defect, when co-immobilized in alginate microspheres. Alginate is a natural polymer widely used as a biomaterial for cell encapsulation. Human osteoprogenitors (HOP) from bone marrow mesenchymal stem cells were immobilized alone or together with human umbilical vein endothelial cells (HUVEC) inside irradiated, oxidized and RGD-grafted alginate microspheres. Immobilized cells were cultured in dynamic conditions and cell metabolic activity increased during three weeks. The gene expression of alkaline phosphatase and osteocalcin, both specific markers of the osteoblastic phenotype, and mineralization deposits were upregulated in co-immobilized HOPs and HUVECs, comparing to the immobilization of monocultures. VEGF secretion was also increased when HOPs were co-immobilized with HUVECs. Microspheres containing co-cultures were further implanted in a bone defect and bone formation was analysed by μCT and histology at 3 and 6 weeks post-implantation. Mineralization was observed inside and around the implanted microspheres containing the immobilized cells. However, when HOPs were co-immobilized with HUVECs, mineralization significantly increased. These findings demonstrate that co-immobilization of osteogenic and endothelial cells within RGD-grafted alginate microspheres provides a promising strategy for bone tissue engineering. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 38Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.02.033PubMed ID: 19299013Language of Original Document: EnglishCorrespondence Address: Grellier, M.; INSERM, U577, Université Victor Segalen Bordeaux 2, UMR-S577, F-33076 Bordeaux Cedex, France; email: maritie.grellier@inserm.frChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; osteocalcin, 136461-80-8; Alginates; Glucuronic Acid, 576-37-4; Hexuronic Acids; alginic acid, 9005-32-7References: Oreffo, R.O., Triffitt, J.T., Future potentials for using osteogenic stem cells and biomaterials in orthopedics (1999) Bone, 25 (2 SUPPL), pp. 5S-9S;Lubiatowski, P., Kruczynski, J., Gradys, A., Trzeciak, T., Jaroszewski, J., Articular cartilage repair by means of biodegradable scaffolds (2006) Transplant Proc, 38 (1), pp. 320-322; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.J., Barrias, C.C., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28 (25), pp. 3644-3655; Gerber, H.P., Ferrara, N., Angiogenesis and bone growth (2000) Trends Cardiovasc Med, 10 (5), pp. 223-228; Carano, R.A., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discov Today, 8 (21), pp. 980-989; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141 (5), pp. 1667-1674; Guillotin, B., Bourget, C., Remy-Zolgadri, M., Bareille, R., Fernandez, P., Conrad, V., Human primary endothelial cells stimulate human osteoprogenitor cell differentiation (2004) Cell Physiol Biochem, 14 (4-6), pp. 325-332; Villars, F., Bordenave, L., Bareille, R., Amedee, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: role of VEGF? (2000) J Cell Biochem, 79 (4), pp. 672-685; Kaigler, D., Krebsbach, P.H., Wang, Z., West, E.R., Horger, K., Mooney, D.J., Transplanted endothelial cells enhance orthotopic bone regeneration (2006) J Dent Res, 85 (7), pp. 633-637; Sun, H., Qu, Z., Guo, Y., Zang, G., Yang, B., In vitro and in vivo effects of rat kidney vascular endothelial cells on osteogenesis of rat bone marrow mesenchymal stem cells growing on polylactide-glycoli acid (PLGA) scaffolds (2007) Biomed Eng Online, 6, p. 41; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromol Biosci, 6 (8), pp. 623-633; Leal, D., Matsuhiro, B., Rossi, M., Caruso, F., FT-IR spectra of alginic acid block fractions in three species of brown seaweeds (2008) Carbohydr Res, 343 (2), pp. 308-316; Keshaw, H., Forbes, A., Day, R.M., Release of angiogenic growth factors from cells encapsulated in alginate beads with bioactive glass (2005) Biomaterials, 26 (19), pp. 4171-4179; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80 (11), pp. 2025-2029; Abbah, S.A., Lu, W.W., Chan, D., Cheung, K.M., Liu, W.G., Zhao, F., In vitro evaluation of alginate encapsulated adipose-tissue stromal cells for use as injectable bone graft substitute (2006) Biochem Biophys Res Commun, 347 (1), pp. 185-191; Barrias, C.C., Lamghari, M., Granja, P.L., Sa Miranda, M.C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localized delivery of a therapeutic enzyme (2005) J Biomed Mater Res A, 74 (4), pp. 545-552; Durrieu, M.C., Pallu, S., Guillemot, F., Bareille, R., Amedee, J., Baquey, C.H., Grafting RGD containing peptides onto hydroxyapatite to promote osteoblastic cells adhesion (2004) J Mater Sci Mater Med, 15 (7), pp. 779-786; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029; Bordenave, L., Baquey, C., Bareille, R., Lefebvre, F., Lauroua, C., Guerin, V., Endothelial cell compatibility testing of three different Pellethanes (1993) J Biomed Mater Res, 27 (11), pp. 1367-1381; Rowley, J.A., Mooney, D.J., Alginate type and RGD density control myoblast phenotype (2002) J Biomed Mater Res, 60 (2), pp. 217-223; Villars, F., Guillotin, B., Amedee, T., Dutoya, S., Bordenave, L., Bareille, R., Effect of HUVEC on human osteoprogenitor cell differentiation needs heterotypic gap junction communication (2002) Am J Physiol Cell Physiol, 282 (4), pp. C775-C785; Clarkin, C.E., Emery, R.J., Pitsillides, A.A., Wheeler-Jones, C.P., Evaluation of VEGF-mediated signaling in primary human cells reveals a paracrine action for VEGF in osteoblast-mediated crosstalk to endothelial cells (2007) J Cell Physiol; Cheng, C., Liu, H., Ge, H., Qian, J., Qin, J., Sun, L., Essential role of Src suppressed C kinase substrates in endothelial cell adhesion and spreading (2007) Biochem Biophys Res Commun, 358 (1), pp. 342-348; Gerber, H.P., McMurtrey, A., Kowalski, J., Yan, M., Keyt, B.A., Dixit, V., Vascular endothelial growth factor regulates endothelial cell survival through the phosphatidylinositol 3′-kinase/Akt signal transduction pathway. Requirement for Flk-1/KDR activation (1998) J Biol Chem, 273 (46), pp. 30336-30343; Cross, M.J., Claesson-Welsh, L., FGF and VEGF function in angiogenesis: signalling pathways, biological responses and therapeutic inhibition (2001) Trends Pharmacol Sci, 22 (4), pp. 201-207; Volkmer, E., Drosse, I., Otto, S., Stangelmayer, A., Stengele, M., Kallukalam, B.C., Hypoxia in static and dynamic 3D culture systems for tissue engineering of bone (2008) Tissue Eng Part A, 14 (8), pp. 1331-1340; Stiehler, M., Bunger, C., Baatrup, A., Lind, M., Kassem, M., Mygind, T., Effect of dynamic 3-D culture on proliferation, distribution, and osteogenic differentiation of human mesenchymal stem cells (2008) J Biomed Mater Res A; Mann, V., Huber, C., Kogianni, G., Jones, D., Noble, B., The influence of mechanical stimulation on osteocyte apoptosis and bone viability in human trabecular bone (2006) J Musculoskelet Neuronal Interact, 6 (4), pp. 408-417; Bjerre, L., Bunger, C.E., Kassem, M., Mygind, T., Flow perfusion culture of human mesenchymal stem cells on silicate-substituted tricalcium phosphate scaffolds (2008) Biomaterials, 29 (17), pp. 2616-2627; Bouletreau, P.J., Warren, S.M., Spector, J.A., Peled, Z.M., Gerrets, R.P., Greenwald, J.A., Hypoxia and VEGF up-regulate BMP-2 mRNA and protein expression in microvascular endothelial cells: implications for fracture healing (2002) Plast Reconstr Surg, 109 (7), pp. 2384-2397; Simmons, C.A., Alsberg, E., Hsiong, S., Kim, W.J., Mooney, D.J., Dual growth factor delivery and controlled scaffold degradation enhance in vivo bone formation by transplanted bone marrow stromal cells (2004) Bone, 35 (2), pp. 562-569; Lu, H.H., Vo, J.M., Chin, H.S., Lin, J., Cozin, M., Tsay, R., Controlled delivery of platelet-rich plasma-derived growth factors for bone formation (2008) J Biomed Mater Res A; Yu, H., Vandevord, P.J., Gong, W., Wu, B., Song, Z., Matthew, H.W., Promotion of osteogenesis in tissue-engineered bone by pre-seeding endothelial progenitor cells-derived endothelial cells (2008) J Orthop Res, 26 (8), pp. 1147-1152; Bouhadir, K.H., Lee, K.Y., Alsberg, E., Damm, K.L., Anderson, K.W., Mooney, D.J., Degradation of partially oxidized alginate and its potential application for tissue engineering (2001) Biotechnol Prog, 17 (5), pp. 945-950
Keywords: adult; aged; Alginate; Alginates; alginic acid; alkaline phosphatase; animal tissue; Animals; arginylglycylaspartic acid; article; Bioactivity; Biopolymers; Blood vessel prostheses; Blood Vessels; Bone; Bone and Bones; bone defect; Bone defects; Bone formations; Bone marrow mesenchymal stem cells; bone mineralization; Bone Regeneration; Bone regenerations; bone tissue; Bone tissue engineerings; Calcification, Physiologic; Cell communications; Cell culture; Cell encapsulations; cell function; cell growth; Cell immobilization; Cell membranes; cell metabolism; Cells, Cultured; Co immobilizations; Co-culture; coculture; computer assisted tomography; controlled study; Defects; Dynamic conditions; Endothelial Cells; endothelium cell; gene expression; gene expression regulation; Glucuronic Acid; Grafting (chemical); Hexuronic Acids; histology; human; human cell; Human umbilical vein endothelial cells; Humans; Humulus; immobilized cell; Immobilized cells; in vitro study; in vivo study; In-vitro; In-vivo; irradiation; long bone; Long bones; Mesenchymal stem cell; Metabolic activities; Mice; Mice, Nude; microsphere; Microspheres; Middle Aged; Mineralogy; monoculture; mouse; nonhuman; osteoblast; osteocalcin; Osteogenic; Osteogenic potentials; Osteoprogenitor cells; Osteoprogenitors; Oxidation; Peptides; phenotype; Post implantations; priority journal; Self assembly; Sodium compounds; stem cell transplantation; Stem cells; Tissue engineering; umbilical vein; upregulation; Vascular endothelial growth factor (VEGF); X ray analysis; Young Adult

Engineering endochondral bone: In vitro studies - Oliveira, S.M.; Amaral, I.F.; Barbosa, M.A.; Teixeira, C.C. (Tissue Engineering - Part ATissue Eng. Part A, 2009)
Chitosan scaffolds have been shown to possess biological and mechanical properties suitable for tissue engineering and clinical applications. In the present work, chitosan sponges were evaluated regarding their ability to support cartilage cell proliferation and maturation, which are the first steps in endochondral bone formation. Chitosan sponges were seeded with chondrocytes isolated from chicken embryo sterna. Chondrocyte/chitosan constructs were cultured for 20 days, and treated with retinoic acid (RA) to induce chondrocyte maturation and matrix synthesis. At different time points, samples were collected for microscopic, histological, biochemical, and mechanical analyses. Results show chondrocyte attachment, proliferation, and abundant matrix synthesis, completely obliterating the pores of the sponges. RA treatment caused chondrocyte hypertrophy, characterized by the presence of type X collagen in the extracellular matrix and increased alkaline phosphatase activity. In addition, hypertrophy markedly changed the mechanical properties of the chondrocyte/chitosan constructs. In conclusion, we have developed chitosan sponges with adequate pore structure and mechanical properties to serve as a support for hypertrophic chondrocytes. In parallel studies, we have evaluated the ability of this mature cartilage scaffold to induce endochondral ossification. © Copyright 2009, Mary Ann Liebert, Inc. 2009.
Cited By (since 1996): 19Export Date: 21 November 2012Source: Scopusdoi: 10.1089/ten.tea.2008.0051Language of Original Document: EnglishCorrespondence Address: Teixeira, C. C.; Departments of Basic Science and Craniofacial Biology and of Orthodontics, New York University, College of Dentistry, 345 East 24th St., New York, NY 10010; email: ct40@nyu.eduChemicals/CAS: DNA, 9007-49-2; alkaline phosphatase, 9001-78-9; chitosan, 9012-76-4; retinoic acid, 302-79-4; Alkaline Phosphatase, 3.1.3.1; Chitosan, 9012-76-4; Collagen Type X; DNA, 9007-49-2; Tretinoin, 302-79-4References: Steinemann, S.G., Metal implants and surface reactions (1996) Injury, 27, p. 16;Disegi, J.A., Eschbach, L., Stainless steel in bone surgery (2000) Injury, 31, p. 2; Reitman, R.D., Emerson, R., Higgins, L., Head, W., Thirteen year results of total hip arthroplasty using a tapered titanium femoral component inserted without cement in patients with type C bone (2003) J Arthroplasty, 18, p. 116; Epinette, J.A., Manley, M.T., D'Antonio, J.A., Edidin, A.A., Capello, W.N., A 10-year minimum follow-up of hydroxyapatite-coated threaded cups: Clinical, radiographic and survivorship analyses with comparison to the literature (2003) J Arthroplasty, 18, p. 140; Xynos, I.D., Hukkanen, M.V., Batten, J.J., Buttery, L.D., Hench, L.L., Polak, J.M., Bioglass 45S5 stimulates osteoblast turnover and enhances bone formation in vitro: Implications and applications for bone tissue engineering (2000) Calcif Tissue Int, 67, p. 321; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Bioceramics, 254, p. 877; Saito, N., Takaoka, K., New synthetic biodegradable polymers as BMP carriers for bone tissue engineering (2003) Biomaterials, 24, p. 2287; Suzuki, T., Kawamura, H., Kasahara, T., Nagasaka, H., Resorbable poly-L-lactide plates and screws for the treatment of mandibular condylar process fractures: A clinical and radiologic follow-up study (2004) J Oral Maxillofac Surg, 62, p. 919; Sittinger, M., Reitzel, D., Dauner, M., Hierlemann, H., Hammer, C., Kastenbauer, E., Planck, H., Bujia, J., Resorbable polyesters in cartilage engineering: Affinity and biocompatibility of polymer fiber structures to chondrocytes (1996) J Biomed Mater Res, 33, p. 57; Vaccaro, A.R., Singh, K., Haid, R., Kitchel, S., Wuisman, P., Taylor, W., Branch, C., Garfin, S., The use of bioabsorbable implants in the spine (2003) Spine J, 3, p. 227; Jianqi, H., Hong, H., Lieping, S., Genghua, G., Comparison of calcium alginate film with collagen membrane for guided bone regeneration in mandibular defects in rabbits (2002) J Oral Maxillofac Surg, 60, p. 1449; Chan, C., Thompson, I., Robinson, P., Wilson, J., Hench, L., Evaluation of bioglass/dextran composite as a bone graft substitute (2002) Int J Oral Maxillofac Surg, 31, p. 73; Mukherjee, D.P., Tunkle, A.S., Roberts, R.A., Clavenna, A., Rogers, S., Smith, D., An animal evaluation of a paste of chitosan glutamate and hydroxyapatite as a synthetic bone graft material (2003) J Biomed Mater Res B Appl Biomater, 67 B, p. 603; Sashiwa, H., Aiba, S., Chemically modified chitin and chitosan as biomaterials (2004) Prog Polym Sci, 89, p. 887; Hoekstra, A., Struszczyk, H., Kivekas, O., Percutaneous microcrystalline chitosan application for sealing arterial puncture sites (1998) Biomaterials, 19, p. 1467; Lee, K.Y., Ha, W.S., Park, W.H., Blood compatibility and biodegradability of partially N-acylated chitosan derivatives (1995) Biomaterials, 16, p. 1211; Suh, J.K., Matthew, H.W., Application of chitosan-based polysaccharide biomaterials in cartilage tissue engineering: A review (2000) Biomaterials, 21, p. 2589; Hirano, S., Tsuchida, H., Nagao, N., N-acetylation in chitosan and the rate of its enzymic hydrolysis (1989) Biomaterials, 10, p. 574; Prashanth, K.V.H., Tharanathan, R.N., Chitin/chitosan: Modifications and their unlimited application potential-an overview (2007) Trends Food Sci Technol, 18, p. 117; Chellat, F., Tabrizian, M., Dumitriu, S., Chornet, E., Hilaire, C., Yahia, R., Study of biodegradation behavior of chitosan-xanthan microspheres in simulated physiological media (2000) J Biomed Mater Res, 53, p. 592; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., Chitosan supports the expression of extracellular matrix proteins in human osteoblasts and chondrocytes (2000) J Biomed Mater Res, 51, p. 586; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Eng, 8, p. 1009; Lu, J.X., Prudhommeaux, F., Meunier, A., Sedel, L., Guillemin, G., Effects of chitosan on rat knee cartilages (1999) Biomaterials, 20, p. 1937; Abe, M., Takahashi, M., Tokura, S., Tamura, H., Nagano, A., Cartilage-scaffold composites produced by bioresorbable beta-chitin sponge with cultured rabbit chondrocytes (2004) Tissue Eng, 10, p. 585; Sechriest, V.F., Miao, Y.J., Niyibizi, C., Westerhausen-Larson, A., Matthew, H.W., Evans, C.H., Fu, F.H., Suh, J.K., GAGaugmented polysaccharide hydrogel: A novel biocompatible and biodegradable material to support chondrogenesis (2000) J Biomed Mater Res, 49, p. 534; Rajpurohit, R., Koch, C.J., Tao, Z., Teixeira, C.M., Shapiro, I.M., Adaptation of chondrocytes to low oxygen tension: Relationship between hypoxia and cellular metabolism (1996) J Cell Physiol, 168, p. 424; Maes, C., Carmeliet, P., Moermans, K., Stockmans, I., Smets, N., Collen, D., Bouillon, R., Carmeliet, G., Impaired angiogenesis and endochondral bone formation in mice lacking the vascular endothelial growth factor isoforms VEGF164 and VEGF188 (2002) Mech Dev, 111, p. 61; Petersen, W., Tsokos, M., Pufe, T., Expression of VEGF121 and VEGF165 in hypertrophic chondrocytes of the human growth plate and epiphyseal cartilage (2002) J Anat, 201, p. 153; Pullig, O., Weseloh, G., Ronneberger, D., Kakonen, S., Swoboda, B., Chondrocyte differentiation in human osteoarthritis: Expression of osteocalcin in normal and osteoarthritic cartilage and bone (2000) Calcif Tissue Int, 67, p. 230; Hashimoto, S., Ochs, R.L., Rosen, F., Quach, J., McCabe, G., Solan, J., Seegmiller, J.E., Lotz, M., Chondrocyte-derived apoptotic bodies and calcification of articular cartilage (1998) Proc Natl Acad Sci USA, 95, p. 3094; Pullig, O., Weseloh, G., Gauer, S., Swoboda, B., Osteopontin is expressed by adult human osteoarthritic chondrocytes: Protein andmRNAanalysis of normal and osteoarthritic cartilage (2000) Matrix Biol, 19, p. 245; Eerola, I., Salminen, H., Lammi, P., Lammi, M., von der Mark, K., Vuorio, E., Saamanen, A.M., Type X collagen, a natural component of mouse articular cartilage: Association with growth, aging, and osteoarthritis (1998) Arthritis Rheum, 41, p. 1287; Amaral, I.F., Sampaio, P., Barbosa, M.A., Threedimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2006) J Biomed Mater Res A, 76, p. 335; Mow, V.C., Kuei, S.C., Lai, W.M., Armstrong, C.G., Biphasic creep and stress relaxation of articular cartilage in compression? Theory and experiments (1980) J Biomech Eng, 102, p. 73; Iwamoto, M., Shapiro, I.M., Yagami, K., Boskey, A.L., Leboy, P.S., Adams, S.L., Pacifici, M., Retinoic acid induces rapid mineralization and expression of mineralizationrelated genes in chondrocytes (1993) Exp Cell Res, 207, p. 413; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein content, and alkaline phosphatase activity of chondrocyte cultures (1995) Calcif Tissue Int, 56, p. 252; Nehrer, S., Breinan, H.A., Ramappa, A., Young, G., Shortkroff, S., Louie, L.K., Sledge, C.B., Spector, M., Matrix collagen type and pore size influence behaviour of seeded canine chondrocytes (1997) Biomaterials, 18, p. 769; Karande, T.S., Ong, J.L., Agrawal, C.M., Diffusion in musculoskeletal tissue engineering scaffolds: Design issues related to porosity, permeability, architecture, and nutrient mixing (2004) Ann Biomed Eng, 32, p. 1728; VandeVord, P.J., Matthew, H.W., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59, p. 585; Hong, Y., Song, H., Gong, Y., Mao, Z., Gao, C., Shen, J., Covalently crosslinked chitosan hydrogel: Properties of in vitro degradation and chondrocyte encapsulation (2007) Acta Biomater, 3, p. 23; Ho, M., Wang, D., Hsieh, H., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., Preparation and characterization of RGDimmobilized chitosan scaffolds (2005) Biomaterials, 26, p. 3197; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) J Biomater Sci Polym Ed, 18, p. 469; Hoemann, C.D., Sun, J., Legare, A., McKee, M.D., Buschmann, M.D., Tissue engineering of cartilage using an injectable and adhesive chitosan-based cell-delivery vehicle (2005) Osteoarthritis Cartilage, 13, p. 318; Griffon, D.J., Sedighi, M.R., Schaeffer, D.V., Eurell, J.A., Johnson, A.L., Chitosan scaffolds: Interconnective pore size and cartilage engineering (2006) Acta Biomater, 2, p. 313; Underhill, T.M., Weston, A.D., Retinoids and their receptors in skeletal development (1998) Microsc Res Tech, 43, p. 137; Cohen, A.J., Lassova, L., Golden, E.B., Niu, Z., Adams, S.L., Retinoids directly activate the collagen X promoter in prehypertrophic chondrocytes through a distal retinoic acid response element (2006) J Cell Biochem, 99, p. 269; Pacifici, M., Golden, E.B., Iwamoto, M., Adams, S.L., Retinoic acid treatment induces type X collagen gene expression in cultured chick chondrocytes (1991) Exp Cell Res, 195, p. 38; Gentili, C., Bianco, P., Neri, M., Malpeli, M., Campanile, G., Castagnola, P., Cancedda, R., Cancedda, F.D., Cellproliferation, extracellular-matrix mineralization, and ovotransferrin transient expression during in-vitro differentiation of chick hypertrophic chondrocytes into osteoblast-like cells (1993) J Cell Biol, 122, p. 703; Naumann, A., Dennis, J.E., Awadallah, A., Carrino, D.A., Mansour, J.M., Kastenbauer, E., Caplan, A.I., Immunochemical and mechanical characterization of cartilage subtypes in rabbit (2002) J Histochem Cytochem, 50, p. 1049; Wang, W., Kirsch, T., Retinoic acid stimulates annexinmediated growth plate chondrocyte mineralization (2002) J Cell Biol, 157, p. 1061; Whyte, M.P., Hypophosphatasia and the role of alkaline phosphatase in skeletal mineralization (1994) Endocr Rev, 15, p. 439; Lewinson, D., Toister, Z., Silbermann, M., Quantitative and distributional changes in the activity of alkaline phosphatase during the maturation of cartilage (1982) J Histochem Cytochem, 30, p. 261; Amaral, I.F., Sampaio, P., Barbosa, M.A., Threedimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2005) J Biomed Mater Res A, 76, p. 335; Park, J.H., Park, B.H., Kim, H.K., Park, T.S., Baek, H.S., Hypoxia decreases Runx2/Cbfa1 expression in human osteoblast-like cells (2002) Mol Cell Endocrinol, 192, p. 197; Utting, J.C., Robins, S.P., Brandao-Burch, A., Orriss, I.R., Behar, J., Arnett, T.R., Hypoxia inhibits the growth, differentiation and bone-forming capacity of rat osteoblasts (2006) Exp Cell Res, 312, p. 1693; Warren, S.M., Steinbrech, D.S., Mehrara, B.J., Saadeh, P.B., Greenwald, J.A., Spector, J.A., Bouletreau, P.J., Longaker, M.T., Hypoxia regulates osteoblast gene expression (2001) J Surg Res, 99, p. 147; Salim, A., Nacamuli, R.P., Morgan, E.F., Giaccia, A.J., Longaker, M.T., Transient changes in oxygen tension inhibit osteogenic differentiation and Runx2 expression in osteoblasts (2004) J Biol Chem, 279, p. 40007; Vu, T.H., Shipley, J.M., Bergers, G., Berger, J.E., Helms, J.A., Hanahan, D., Shapiro, S.D., Werb, Z., MMP-9/gelatinase B is a key regulator of growth plate angiogenesis and apoptosis of hypertrophic chondrocytes (1998) Cell, 93, p. 411; Skawina, A., Litwin, J.A., Gorczyca, J., Miodonski, A.J., The vascular system of human fetal long bones: A scanning electron microscope study of corrosion casts (1994) J Anat, 185, p. 369; Pfander, D., Cramer, T., Schipani, E., Johnson, R.S., HIF-1alpha controls extracellular matrix synthesis by epiphyseal chondrocytes (2003) J Cell Sci, 116, p. 1819; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141, p. 1667; Gerber, H.P., Vu, T.H., Ryan, A.M., Kowalski, J., Werb, Z., Ferrara, N., VEGF couples hypertrophic cartilage remodeling, ossification and angiogenesis during endochondral bone formation (1999) Nat Med, 5, p. 623; Nakagawa, M., Kaneda, T., Arakawa, T., Morita, S., Sato, T., Yomada, T., Hanada, K., Hakeda, Y., Vascular endothelial growth factor (VEGF) directly enhances osteoclastic bone resorption and survival of mature osteoclasts (2000) FEBS Lett, 473, p. 161; Pfander, D., Kortje, D., Zimmermann, R., Weseloh, G., Kirsch, T., Gesslein, M., Cramer, T., Swoboda, B., Vascular endothelial growth factor in articular cartilage of healthy and osteoarthritic human knee joints (2001) Ann RheumDis, 60, p. 1070; Oliveira, S.M., Turner, G., Mijares, D., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., (2007) Engineering endochondral bone: In vivo studies
Keywords: alkaline phosphatase; Alkaline phosphatase activity; animal; animal cell; animal tissue; Animals; article; biomechanics; Body fluids; Bone; Bone and Bones; Bone formation; Cartilage; cartilage cell; Cell culture; cell damage; cell hypertrophy; cell isolation; cell maturation; Cell membranes; cell proliferation; Cells, Cultured; chick embryo; Chicken embryo; Chitin; chitosan; Chitosan scaffold; Chondrocyte; Chondrocyte maturation; Chondrocytes; Clinical application; collagen type 10; Collagen Type X; controlled study; cytology; DNA; drug effect; embryo; enchondral ossification; Endochondral ossification; enzyme activity; enzymology; Extracellular matrices; extracellular matrix; gene expression profiling; Hypertrophic chondrocytes; in vitro study; In-vitro; Ligaments; Matrix synthesis; Mechanical analysis; Mechanical properties; metabolism; methodology; nonhuman; Pathology; physiology; Porifera; porosity; priority journal; retinoic acid; Retinoic acids; Scaffolds; sponge (Porifera); Sterna; sternum; synthesis; Time points; Tissue engineering; tissue scaffold; Tissue Scaffolds; Tretinoin; Type X collagen

Engineering endochondral bone: In vivo studies - Oliveira, S.M.; Mijares, D.Q.; Turner, G.; Amaral, I.F.; Barbosa, M.A.; Teixeira, C.C. (Tissue Engineering - Part ATissue Eng. Part A, 2009)
The use of biomaterials to replace lost bone has been a common practice for decades. More recently, the demands for bone repair and regeneration have pushed research into the use of cultured cells and growth factors in association with these materials. Here we report a novel approach to engineer new bone using a transient cartilage scaffold to induce endochondral ossification. Chondrocyte/chitosan scaffolds (both a transient cartilage scaffold- experimental-and a permanent cartilage scaffold-control) were prepared and implanted subcutaneously in nude mice. Bone formation was evaluated over a period of 5 months. Mineralization was assessed by Faxitron, micro computed tomography, backscatter electrons, and Fourier transform infrared spectroscopy analyses. Histological analysis provided further information on tissue changes in and around the implanted scaffolds. The deposition of ectopic bone was detected in the surface of the experimental implants as early as 1 month after implantation. After 3 months, bone trabeculae and bone marrow cavities were formed inside the scaffolds. The bone deposited was similar to the bone of the mice vertebra. Interestingly, no bone formation was observed in control implants. In conclusion, an engineered transient cartilage template carries all the signals necessary to induce endochondral bone formation in vivo. © Copyright 2009, Mary Ann Liebert, Inc. 2009.
Cited By (since 1996): 14Export Date: 21 November 2012Source: Scopusdoi: 10.1089/ten.tea.2008.0052Language of Original Document: EnglishCorrespondence Address: Teixeira, C. C.; Department of Basic Science and Craniofacial Biology, College of Dentistry, New York University, 345 East. 24th St., New York, NY 10010; email: ct40@nyu.eduChemicals/CAS: chitosan, 9012-76-4; Chitosan, 9012-76-4; MineralsReferences: Yelin, E., Callahan, L.F., The economic cost and social and psychological impact of musculoskeletal conditions. National Arthritis Data Work Groups (1995) Arthritis Rheum, 38, p. 1351;Service, R.F. Tissue engineers build new bone. Science 289,1498, 2000Dupraz, A., Delecrin, J., Moreau, A., Pilet, P., Passuti, N., Long-term bone response to particulate injectable ceramic (1998) J Biomed Mater Res, 42, p. 368; Gauthier, O., Khairoun, I., Bosco, J., Obadia, L., Bourges, X., Rau, C., Magne, D., Daculsi, G., Noninvasive bone replacement with a new injectable calcium phosphate biomaterial (2003) J Biomed Mater Res, 66 A, p. 47; Maroudas, A., Bayliss, M.T., Uchitel-Kaushansky, N., Schneiderman, R., Gilav, E., Aggrecan turnover in human articular cartilage: Use of aspartic acid racemization as a marker of molecular age (1998) Arch Biochem Biophys, 350, p. 61; Ferguson, C., Alpern, E., Miclau, T., Helms, J.A., Does adult fracture repair recapitulate embryonic skeletal formation? (1999) Mech Dev, 87, p. 57; Iwamoto, M., Higuchi, Y., Enomoto-Iwamoto, M., Kurisu, K., Koyama, E., Yeh, H., Rosenbloom, J., Pacifici, M., The role of ERG (ets related gene) in cartilage development (2001) Osteoarthr Cartil, 9 (SUPPL. A), pp. S41; Montufar-Solis, D., Nguyen, H.C., Nguyen, H.D., Horn, W.N., Cody, D.D., Duke, P.J., Using cartilage to repair bone: An alternative approach in tissue engineering (2004) Ann Biomed Eng, 32, p. 504; Pountos, I., Jones, E., Tzioupis, C., McGonagle, D., Giannoudis, P.V., Growing bone and cartilage: The role of mesenchymal stem cells (2006) J Bone Joint Surg Br, 88, p. 421; Valimaki, V.V., Yrjans, J.J., Vuorio, E.I., Aro, H.T., Molecular biological evaluation of bioactive glass microspheres and adjunct bone morphogenetic protein 2 gene transfer in the enhancement of new bone formation (2005) Tissue Eng, 11, p. 387; Huang, Y.C., Simmons, C., Kaigler, D., Rice, K.G., Mooney, D.J., Bone regeneration in a rat cranial defect with delivery of PEI-condensed plasmid DNA encoding for bone morphogenetic protein-4 (BMP-4) (2005) Gene Ther, 12, p. 418; Bikram, M., Fouletier-Dilling, C., Hipp, J.A., Gannon, F., Davis, A.R., Olmsted-Davis, E.A., West, J.L., Endochondral bone formation from hydrogel carriers loaded with BMP2-transduced cells (2007) Ann Biomed Eng, 35, p. 796; Alsberg, E., Anderson, K.W., Albeiruti, A., Rowley, J.A., Mooney, D.J., Engineering growing tissues (2002) Proc Natl Acad Sci USA, 99, p. 12025; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141, p. 1667; Petersen, W., Tsokos, M., Pufe, T., Expression of VEGF121 and VEGF165 in hypertrophic chondrocytes of the human growth plate and epiphyseal cartilage (2002) J Anat, 201, p. 153; Nakagawa, M., Kaneda, T., Arakawa, T., Morita, S., Sato, T., Yomada, T., Hanada, K., Hakeda, Y., Vascular endothelial growth factor (VEGF) directly enhances osteoclastic bone resorption and survival of mature osteoclasts (2000) FEBS Lett, 473, p. 161; Gerber, H.P., Vu, T.H., Ryan, A.M., Kowalski, J., Werb, Z., Ferrara, N., VEGF couples hypertrophic cartilage remodeling, ossification and angiogenesis during endochondral bone formation (1999) Nat Med, 5, p. 623; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., (2007) Engineering endochondral bone: In vitro studies; Hasegawa, S., Ishii, S., Tamura, J., Furukawa, T., Neo, M., Matsusue, Y., Shikinami, Y., Nakamura, T., A 5-7 year in vivo study of high-strength hydroxyapatite/ poly(L-lactide) composite rods for the internal fixation of bone fractures (2006) Biomaterials, 27, p. 1327; Gauthier, O., Muller, R., von Stechow, D., Lamy, B., Weiss, P., Bouler, J.M., Aguado, E., Daculsi, G., In vivo bone regeneration with injectable calcium phosphate biomaterial: A three-dimensional micro-computed tomographic, biomechanical and SEM study (2005) Biomaterials, 26, p. 5444; Chan, C., Thompson, I., Robinson, P., Wilson, J., Hench, L., Evaluation of Bioglass/dextran composite as a bone graft substitute (2002) Int J Oral Maxillofac Surg, 31, p. 73; Trojani, C., Boukhechba, F., Scimeca, J.C., Vandenbos, F., Michiels, J.F., Daculsi, G., Boileau, P., Rochet, N., Ectopic bone formation using an injectable biphasic calcium phosphate/Si-HPMC hydrogel composite loaded with undifferentiated bone marrow stromal cells (2006) Biomaterials, 27, p. 3256; van Gaalen, S.M., Dhert, W.J.A., van den Muysenberg, A., Oner, F.C., van Blitterswijk, C., Verbout, A.J., de Bruijn, J.D., Bone tissue engineering for spine fusion: An experimental study on ectopic and orthotopic implants in rats (2004) Tissue Eng, 10, p. 231; Kim, H., Suh, H., Jo, S.A., Kim, H.W., Lee, J.M., Kim, E.H., Reinwald, Y., Jo, I., In vivo bone formation by human marrow stromal cells in biodegradable scaffolds that release dexamethasone and ascorbate-2-phosphate (2005) Biochem Biophys Res Commun, 332, p. 1053; Krebsbach, P.H., Kuznetsov, S.A., Satomura, K., Emmons, R.V.B., Rowe, D.W., Robey, P.G., Bone formation in vivo: Comparison of osteogenesis by transplanted mouse and human marrow stromal fibroblasts (1997) Transplantation, 63, p. 1059; Musgrave, D.S., Bosch, P., Lee, J.Y., Pelinkovic, D., Ghivizzani, S.C., Whalen, J., Niyibizi, C., Huard, J., Ex vivogene therapy to produce bone using different cell types (2000) Clin Orthop Relat Res, 378, p. 290; Kojima, K., Bonassar, L.J., Ignotz, R.A., Syed, K., Cortiella, J., Vacanti, C.A., Comparison of tracheal and nasal chondrocytes for tissue engineering of the trachea (2003) Ann Thorac Surg, 76, p. 1884; van Susante, J.L., Buma, P., Homminga, G.N., van den Berg, W.B., Veth, R.P., Chondrocyte-seeded hydroxyapatite for repair of large articular cartilage defects: A pilot study in the goat (1998) Biomaterials, 19, p. 2367; Lu, J.X., Prudhommeaux, F., Meunier, A., Sedel, L., Guillemin, G., Effects of chitosan on rat knee cartilages (1999) Biomaterials, 20, p. 1937; Dorotka, R., Windberger, U., Macfelda, K., Bindreiter, U., Toma, C., Nehrer, S., Repair of articular cartilage defects treated by microfracture and a three-dimensional collagen matrix (2005) Biomaterials, 26, p. 3617; Marijnissen, W.J.C.M., van Osch, G.J.V.M., Aigner, J., Verwoerd-Verhoef, H.L., Verhaar, J.A.N., Tissueengineered cartilage using serially passaged articular chondrocytes. Chondrocytes in alginate, combined in vivo with a synthetic (E210) or biologic biodegradable carrier (DBM) (2000) Biomaterials, 21, p. 571; Case, N.D., Duty, A.O., Ratcliffe, A., Muller, R., Guldberg, R.E., Bone formation on tissue-engineered cartilage constructs in vivo: Effects of chondrocyte viability and mechanical loading (2003) Tissue Eng, 9, p. 587; Cancedda, R., Cancedda, F.D., Castagnola, P., Chondrocyte differentiation (1995) Int Rev Cytol, 159, p. 265; Hunziker, E.B., Mechanism of longitudinal bone-growth and its regulation by growth-plate chondrocytes (1994) Microsc Res Tech, 28, p. 505; Kirsch, T., Nah, H.D., Shapiro, I.M., Pacifici, M., Regulated production of mineralization-competent matrix vesicles in hypertrophic chondrocytes (1997) J Cell Biol, 137, p. 1149; Anderson, H.C., Molecular-biology of matrix vesicles (1995) Clin Orthop Relat Res, 314, p. 266; Yaylaoglu, M.B., Yildiz, C., Korkusuz, F., Hasirci, V., A novel osteochondral implant (1999) Biomaterials, 20, p. 1513; Garimella, R., Bi, X.H., Camacho, N., Sipe, J.B., Anderson, H.C., Primary culture of rat growth plate chondrocytes: An in vitro model of growth plate histotype, matrix vesicle biogenesis and mineralization (2004) Bone, 34, p. 961; Boskey, A., Camacho, N.P., FT-IR imaging of native and tissue-engineered bone and cartilage (2007) Biomaterials, 28, p. 2465; Jikko, A., Aoba, T., Murakami, H., Takano, Y., Iwamoto, M., Kato, Y., Characterization of the mineralization process in cultures of rabbit growth plate chondrocytes (1993) Dev Biol, 156, p. 372; Cadet, E.R., Gafni, R.I., McCarthy, E.F., McCray, D.R., Bacher, J.D., Barnes, K.M., Baron, J., Mechanisms responsible for longitudinal growth of the cortex: Coalescence of trabecular bone into cortical bone (2003) J Bone Joint Surg Am, 85 A, p. 1739; Lee, C., Grad, S., Wimmer, M., Alini, M., The influence of mechanical stimuli on articular cartilage tissue engineering (2006) Cartilage Tissue Eng, 2, p. 1; Trepczik, B., Lienau, J., Schell, H., Epari, D.R., Thompson, M.S., Hoffmann, J.E., Kadow-Romacker, A., Duda, G.N., Endochondral ossification in vitro is influenced by mechanical bending (2007) Bone, 40, p. 597; Tanck, E., Hannink, G., Ruimerman, R., Buma, P., Burger, E.H., Huiskes, R., Cortical bone development under the growth plate is regulated by mechanical load transfer (2006) J Anat, 208, p. 73; Dong, J., Uemura, T., Kojima, H., Kikuchi, M., Tanaka, J., Tateishi, T., Application of low-pressure system to sustain in vivo bone formation in osteoblast/porous hydroxyapatite composite (2001) DNLM, 17, p. 37; Stevens, M., Marini, R., Schaefer, D., Aronson, J., Langer, R., Shastri, V., In vivo engineering of organs: The bone bioreactor (2005) Proc Natl Acad Sci USA, 102, p. 11450; Rinaudo, M., Chitin and chitosan: Properties and applications (2006) Prog Polym Sci, 31, p. 603
Keywords: animal; animal experiment; animal tissue; Animals; article; Biological materials; Biomaterials; Bone; Bone and Bones; Bone formation; bone marrow; bone mineralization; Bone repair; bone transplantation; Calcification, Physiologic; Cartilage; cartilage cell; chick embryo; chitosan; Chondrocytes; Computerized tomography; controlled study; Cultured cell; cytology; drug effect; Ectopic bones; ectopic tissue; electron; enchondral ossification; Endochondral ossification; Fourier transform infrared spectroscopy; Growth (materials); Growth factor; Histological analysis; histology; implantation; in vivo study; In-control; In-vivo; infrared spectroscopy; Ligaments; male; metabolism; methodology; Mice; Mice, Nude; micro-computed tomography; Microcomputed tomography; Microscopy, Electron, Scanning; mineral; Minerals; mouse; Mus; Mus musculus; nonhuman; Nude mice; nude mouse; ossification; physiology; priority journal; Prosthesis Implantation; Scaffolds; Scanning electron microscopy; Spectroscopic analysis; Spectroscopy; Spectroscopy, Fourier Transform Infrared; Tissue changes; Tissue engineering; tissue scaffold; Tissue Scaffolds; Tomography; trabecular bone; vertebra

Evaluation of symmetry enhanced sliding band filter for plant cell nuclei detection in low contrast noisy fluorescent images - Marcuzzo, M.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
The study of cell nuclei is fundamental for plant cell Biology research. To obtain information at cellular level, researchers image cells' nuclei which were modified with fluorescence proteins, through laser scanning confocal microscopy. These images are normally noisy and suffer from high background fluorescence, making grey-scale segmentation approaches inadequate for a usable detection. To obtain a successful detection even at low contrast we investigate the use of a particular convergence filter, the Symmetric Sliding Band filter (SSBF), for cell detection. This filter is based on gradient convergence and not intensity. As such it can detect low contrast cell nuclei which otherwise would be lost in the background noise. Due to the characteristics of cell nuclei morphology, a symmetry constrain is integrated in the filter which corrects some inadequate detections and results in a filter response that is more discriminative. We evaluate the use of this filter for cell nuclei detection on the Arabidopsis thaliana root tip, where the nuclei were stained using yellow fluorescence protein. The resulting cell nuclei detection precision is 89%. © 2009 Springer Berlin Heidelberg.
Conference code: 77746Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-02611-9_81Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica Divisão de Sinal e Imagem, Campus FEUPReferences: Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res, 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A.: Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo. In: Motion 2007, p. 13 (2007)Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Willemse, J., Kulikova, O., de Jong, H., Bisseling, T., A new whole-mount dna quantification method and the analysis of nuclear dna content in the stem-cell niche of arabidopsis roots (2008) The Plant Journal, 10, pp. 1365-1374; Chen, X., Zhou, X., Wong, S.T.C., Automated segmentation, classification, and tracking of cancer cell nuclei in time-lapse microscopy (2006) IEEE Trans. on Biomedical Engineering, 53 (4), pp. 762-766; Mao, K.Z., Zhao, P., Tan, P., Supervised learning-based cell image segmentation for p53 immunohistochemistry (2006) IEEE Trans. on Biomedical Engineering, 53 (6), pp. 1153-1163; Schmitt, M.H.O., Morphological multiscale decomposition of connected regions with emphasis on cell clusters (2009) Computer Vision and Image Understanding, 113, pp. 188-201; Yang, X., Li, H., Zhou, X., Nuclei segmentation using marker-controlled watershed, tracking using mean-shift, and kalman filter in time-lapse microscopy (2006) IEEE Trans. on Circuits and Systems I-Regul. Papers, 53 (11), pp. 2405-2414; Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Trans. on Image Processing, 8 (8); Wei, J., Hagihara, Y., Kobatake, H., Detection of rounded opacities on chest radiographs using convergence index filter (1999) Proceedings of the Int. Conference on Image Analysis and Processing, pp. 757-761;
Keywords: Arabidopsis thaliana; Background noise; Band filters; Bioinformatics; Biology imaging; Cell detection; Cell membranes; cell nucleus; Cellular levels; confocal microscopy; Convergence filters; cytology; Filter response; Fluorescence; Fluorescence proteins; Fluorescent images; Image analysis; Laser scanning confocal microscopy; Low contrast; Plant cell culture; Plant cells; Positron emission tomography; Root tip; Yellow fluorescence proteins

Fibronectin-mediated endothelialisation of chitosan porous matrices - Amaral, I.F.; Unger, R.E.; Fuchs, S.; Mendonça, A.M.; Sousa, S.R.; Barbosa, M.A.; Pêgo, A.P.; Kirkpatrick, C.J. (BiomaterialsBiomaterials, 2009)
Chitosan (Ch) porous matrices were investigated regarding their ability to be colonized by human microvascular endothelial cells (HPMEC-ST1.6R cell line) and macrovascular endothelial cells namely HUVECs. Specifically we assessed if previous incubation of Ch in a fibronectin (FN) solution was effective in promoting endothelial cell (EC) adhesion to Ch matrices with different degrees of acetylation (DAs). Upon FN physiadsorption, marked differences were found between the two DAs investigated, namely DA 4% and 15%. While cell adhesion was impaired on Ch with DA 15%, ECs were able to not only adhere to Ch with DA 4%, but also to spread and colonize the scaffolds, with retention of the EC phenotype and angiogenic potential. To explain the observed differences between the two DAs, protein adsorption studies using 125I-FN and immunofluorescent labelling of FN cell-binding domains were carried out. In agreement with the higher cell numbers found, scaffolds with DA 4% revealed a higher number of exposed FN cell-binding domains as well as greater ability to adsorb FN and to retain and exchange adsorbed FN in the presence of competitive proteins. These findings suggest that the DA is a key parameter modulating EC adhesion to FN-coated Ch by influencing the adsorbed protein layer. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.06.056PubMed ID: 19615736Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; fibronectin, 86088-83-7; Biocompatible Materials; Chitosan, 9012-76-4; FibronectinsReferences: Moon, J.J., West, J.L., Vascularization of engineered tissues: approaches to promote angiogenesis in biomaterials (2008) Current Topics in Medicinal Chemistry, 8 (4), pp. 300-310;Blitterswijk, C.A., Moroni, L., Rouwkema, J., Siddappa, R., Sohier, J., Tissue engineering - an introduction (2008) Tissue engineering, , Blitterswijk C.A. (Ed), Elsevier; Ehrbar, M., Zeisberger, S.M., Raeber, G.P., Hubbell, J.A., Schnell, C., Zisch, A.H., The role of actively released fibrin-conjugated VEGF for VEGF receptor 2 gene activation and the enhancement of angiogenesis (2008) Biomaterials, 29 (11), pp. 1720-1729; Elbjeirami, W.M., West, J.L., Angiogenesis-like activity of endothelial cells co-cultured with VEGF-producing smooth muscle cells (2006) Tissue Engineering, 12 (2), pp. 381-390; Unger, R.E., Peters, K., Wolf, M., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Endothelialization of a non-woven silk fibroin net for use in tissue engineering: growth and gene regulation of hunian endothelial cells (2004) Biomaterials, 25 (21), pp. 5137-5146; Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Outgrowth endothelial cells isolated and expanded from human peripheral blood progenitor cells as a potential source of autologous cells for endothelialization of silk fibroin biomaterials (2006) Biomaterials, 27 (31), pp. 5399-5408; Kirkpatrick, C.J., Unger, R.E., Krump-Konvalinkova, V., Peters, K., Schmidt, H., Kamp, G., Experimental approaches to study vascularization in tissue engineering and biomaterial applications (2003) Journal of Materials Science, 14 (8), pp. 677-681; Calonder, C., Matthew, H.W.T., Van Tassel, P.R., Adsorbed layers of oriented fibronectin: a strategy to control cell-surface interactions (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 316-323; Kouvroukoglou, S., Dee, K.C., Bizios, R., McIntire, L.V., Zygourakis, K., Endothelial cell migration on surfaces modified with immobilized adhesive peptides (2000) Biomaterials, 21 (17), pp. 1725-1733; Burdick, J.A., Khademhosseini, A., Langer, R., Fabrication of gradient hydrogels using a microfluidics/photopolymerization process (2004) Langmuir, 20 (13), pp. 5153-5156; Garcia, A.J., Get a grip: integrins in cell-biomaterial interactions (2005) Biomaterials, 26, pp. 7525-7529; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18 (7), pp. 567-575; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cells osteogenic differentiation and fibronectin adsorption on chitosan membranes: the effect of the degree of acetylation (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 387-397; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Engineering, 8 (6), pp. 1009-1016; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: in vitro studies (2009) Tissue Engineering, 15 (3), pp. 625-634; Freier, T., Koh, H.S., Kazazian, K., Shoichet, M.S., Controlling cell adhesion and degradation of chitosan films by N-acetylation (2005) Biomaterials, 26 (29), pp. 5872-5878; Wang, X.H., Cui, F.Z., Feng, Q.L., Li, J.C., Zhang, Y.H., Preparation and characterization of collagen/chitosan matrices as potential biomaterials (2003) Journal of Bioactive and Compatible Polymers, 18 (6), pp. 453-467; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., Vascular cell responses to polysaccharide materials: in vitro and in vivo evaluations (2000) Biomaterials, 21 (22), pp. 2315-2322; Chung, T.W., Lu, Y.F., Wang, S.S., Lin, Y.S., Chu, S.H., Growth of human endothelial cells on photochemically grafted Gly-Arg-Gly-Asp (GRGD) chitosans (2002) Biomaterials, 23 (24), pp. 4803-4809; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: consequences for valve endothelial cell growth on tissue-engineering materials (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 538-547; Huang, Y., Onyeri, S., Siewe, M., Moshfeghian, A., Madihally, S.V., In vitro characterization of chitosan-gelatin scaffolds for tissue engineering (2005) Biomaterials, 26 (36), pp. 7616-7627; Huang, Y., Siewe, M., Madilhally, S.V., Effect of spatial architecture on cellular colonization (2006) Biotechnology and Bioengineering, 93 (1), pp. 64-75; Kirsebom, H., Aguilar, M.R., Roman, J.S., Fernandez, M., Prieto, M.A., Bondar, B., Macroporous scaffolds based on chitosan and bioactive molecules (2007) Journal of Bioactive and Compatible Polymers, 22 (6), pp. 621-636; Cao, W.L., Jing, D.H., Li, J.M., Gong, Y.D., Zhao, N.M., Zhang, X.F., Effects of the degree of deacetylation on the physicochemical properties and Schwann cell affinity of chitosan films (2005) Journal of Biomaterials Applications, 20 (2), pp. 157-177; Amaral, I.F., Sampaio, P., Barbosa, M.A., Three-dimensional culture of human osteoblastic cells in chitosan sponges: the effect of the degree of acetylation (2006) Journal of Biomedical Materials Research Part A, 76 A (2), pp. 335-346; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42 (8), pp. 3569-3580; Vachoud, L., Zydowicz, N., Domard, A., Formation and characterisation of a physical chitin gel (1997) Carbohydrate Research, 302 (3-4), pp. 169-177; Montembault, A., Viton, C., Domard, A., Physico-chemical studies of the gelation of chitosan in a hydroalcoholic medium (2005) Biomaterials, 26 (8), pp. 933-943; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) Journal of Biomaterials Science Polymer Edition, 18 (4), pp. 469-485; Krump-Konvalinkova, V., Bittinger, F., Unger, R.E., Peters, K., Lehr, H.A., Kirkpatrick, C.J., Generation of human pulmonary microvascular endothelial cell lines (2001) Laboratory Investigation, 81 (12), pp. 1717-1727; Unger, R.E., Krump-Konvalinkova, V., Peters, K., Kirkpatrick, C.J., In vitro expression of the endothelial phenotype: comparative study of primary isolated cells and cell lines, including the novel cell line HPMEC-ST1.6R (2002) Microvascular Research, 64 (3), pp. 384-397; Jaffe, E.A., Nachman, R.L., Becker, C.G., Minick, C.R., Culture of human endothelial cells derived from umbilical veins. Identification by morphologic and immunologic criteria (1973) J Clin Invest, 52 (11), pp. 2745-2756; O'Brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) European Journal of Biochemistry, 267 (17), pp. 5421-5426; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein-content, and alkaline-phosphatase activity of chondrocyte cultures (1995) Calcified Tissue International, 56 (3), pp. 252-256; Barbosa, J.N., Amaral, I.F., Águas, A.P., Barbosa, M.A., Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds Journal of Biomedical Materials Research Part A, , in press, doi:10.1002/jbm.a.32499; Marshall, A.J., Barker, T., Sage, E.H., Hauch, K.D., Ratner, B.D., (2004) Pore size controls angiogenesis in subcutaneously implanted porous matrices. 7th World Biomaterials Congress; 2004, , Australian Society for Biomaterials Inc., Sydney, Australia p. 710; Unger, R.E., Sartoris, A., Peters, K., Motta, A., Migliaresi, C., Kunkel, M., Tissue-like self-assembly in cocultures of endothelial cells and osteoblasts and the formation of microcapillary-like structures on three-dimensional porous biomaterials (2007) Biomaterials, 28 (27), pp. 3965-3976; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13 (13), pp. 3404-3413; Wendt, D., Marsano, A., Jakob, M., Heberer, M., Martin, I., Oscillating perfusion of cell suspensions through three-dimensional scaffolds enhances cell seeding efficiency and uniformity (2003) Biotechnology and Bioengineering, 84 (2), pp. 205-214; Santos, M.I., Fuchs, S., Gomes, M.E., Unger, R.E., Reis, R.L., Kirkpatrick, C.J., Response of micro- and macrovascular endothelial cells to starch-based fiber meshes for bone tissue engineering (2007) Biomaterials, 28 (2), pp. 240-248; Vestweber, D., Molecular mechanisms that control endothelial cell contacts (2000) Journal of Pathology, 190 (3), pp. 281-291; Mori, T., Irie, Y., Nishimura, S., Tokura, S., Matsuura, M., Okumura, M., Endothelial cell responses to chitin and its derivatives (1998) Journal of Biomedical Materials Research, 43 (4), pp. 469-472; Panetti, T.S., Hannah, D.F., Avraamides, C., Gaughan, J.P., Marcinkiewicz, Z., Huttenlocher, A., Extracellular matrix molecules regulate endothelial cell migration stimulated by lysophosphatidic acid (2004) Journal of Thrombosis and Haemostasis, 2 (9), pp. 1645-1656; Garcia, A.J., Boettiger, D., Integrin-fibronectin interactions at the cell-material interface: initial integrin binding and signaling (1999) Biomaterials, 20 (23-24), pp. 2427-2433; Danen, E.H.J., Sonnenberg, A., Integrins in regulation of tissue development and function (2003) Journal of Pathology, 200 (4), pp. 471-480; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) Journal of Biomedical Materials Research Part A, 66 A (2), pp. 247-259; Renner, L., Jorgensen, B., Markowski, M., Salchert, K., Werner, C., Pompe, T., Control of fibronectin displacement on polymer substrates to influence endothelial cell behaviour (2004) Journal of Materials Science-Materials in Medicine, 15 (4), pp. 387-390; Garcia, A.J., Vega, M.D., Boettiger, D., Modulation of cell proliferation and differentiation through substrate-dependent changes in fibronectin conformation (1999) Molecular Biology of the Cell, 10 (3), pp. 785-798; Koenig, A.L., Gambillara, V., Grainger, D.W., Correlating fibronectin adsorption with endothelial cell adhesion and signaling on polymer substrates (2003) Journal of Biomedical Materials Research Part A, 64 A (1), pp. 20-37; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates focal adhesion composition and signaling through changes in integrin binding (2004) Biomaterials, 25, pp. 5947-5954; Pompe, T., Kobe, F., Salchert, K., Jorgensen, B., Oswald, J., Werner, C., Fibronectin anchorage to polymer substrates controls the initial phase of endothelial cell adhesion (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 647-657
Keywords: Acetylation; Adhesion; Adsorption; angiogenesis; article; Biocompatible Materials; Blood vessel prostheses; cell adhesion; Cell culture; cell invasion; Cell Line; Cell lines; Cell membranes; Cell number; cell proliferation; Cell size; cell spreading; cell survival; Cell-binding domain; Chitin; Chitin/chitosan; chitosan; colony formation; controlled study; Degrees of acetylation; Electric conductivity measurement; Electric currents; Endothelial cell; Endothelial Cells; Endothelialisation; endothelium; endothelium cell; epithelization; Fibronectin; Fibronectins; human; human cell; Human microvascular endothelial cells; Humans; immunofluorescence test; Key parameters; Labels; materials testing; Matrix algebra; Neovascularization, Physiologic; phenotype; porosity; Porous matrixs; priority journal; Protein adsorption; Protein layers; Scaffold; Scaffolds; Self assembly; Tissue engineering; tissue scaffold; umbilical vein

Improving chitosan-mediated gene transfer by the introduction of intracellular buffering moieties into the chitosan backbone - Moreira, C.; Oliveira, H.; Pires, L.R.; Simões, S.; Barbosa, M.A.; Pêgo, A.P. (Acta BiomaterialiaActa Biomater., 2009)
Chitosan was functionalized with imidazole moieties (CHimi) with the aim of improving its buffering capacity and promoting the endosomal escape ability of chitosan-DNA complexes, ultimately increasing their transfection efficiency. 5.6%, 12.9% and 22.1% of the glucosamine residues of chitosan were substituted. Complexes with different molar ratios of primary amines to DNA phosphate anion (N/P) were prepared by a coacervation method. For an N/P > 3, CHimi polymers are able to complex electrostatically with DNA and condense it into positively charged nanostructures (average size 260 nm and zeta potential +16 mV at pH 5.5). In the concentration range 2.5-100 μg ml
Cited By (since 1996): 17Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2009.04.021PubMed ID: 19427930Language of Original Document: EnglishCorrespondence Address: Pêgo, A.P.; INEB-Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: apego@ineb.up.ptChemicals/CAS: DNA, 9007-49-2; chitosan, 9012-76-4; imidazole, 1467-16-9, 288-32-4; Biocompatible Materials; Buffers; Chitosan, 9012-76-4; DNA, 9007-49-2; Drug CarriersReferences: Kirkpatrick, C.J., Fuchs, S., Peters, K., Brochhausen, C., Hermanns, M.I., Unger, R.E., Visions for regenerative medicine: interface between scientific fact and science fiction (2006) Artif Organs, 30, pp. 822-827;Simões, S., Filipe, A., Faneca, H., Mano, M., Penacho, N., Duzgunes, N., Cationic liposomes for gene delivery (2005) Expert Opin Drug Deliv, 2, pp. 237-254; Lungwitz, U., Breunig, M., Blunk, T., Gopferich, A., Polyethylenimine-based non-viral gene delivery systems (2005) Eur J Pharm Biopharm, 60, pp. 247-266; Filion, M.C., Phillips, N.C., Major limitations in the use of cationic liposomes for DNA delivery (1998) Int J Pharm, 162, pp. 159-170; Lv, H., Zhang, S., Wang, B., Cui, S., Yan, J., Toxicity of cationic lipids and cationic polymers in gene delivery (2006) J Control Release, 114, pp. 100-109; Itaka, K., Ohba, S., Miyata, K., Kawaguchi, H., Nakamura, K., Takato, T., Bone regeneration by regulated in vivo gene transfer using biocompatible polyplex nanomicelles (2007) Mol Ther, 15, pp. 1655-1662; Borchard, G., Chitosans for gene delivery (2001) Adv Drug Deliv Rev, 52, pp. 145-150; Khalil, I.A., Kogure, K., Akita, H., Harashima, H., Uptake pathways and subsequent intracellular trafficking in nonviral gene delivery (2006) Pharmacol Rev, 58, pp. 32-45; Behr, J.P., The proton sponge: a trick to enter cells the viruses did not exploit (1997) Chimia, 51, pp. 34-36; Kim, T.H., Kim, S.I., Akaike, T., Cho, C.S., Synergistic effect of poly(ethylenimine) on the transfection efficiency of galactosylated chitosan/DNA complexes (2005) J Control Release, 105, pp. 354-366; Midoux, P., Monsigny, M., Efficient gene transfer by histidylated polylysine/pDNA complexes (1999) Bioconjug Chem, 10, pp. 406-411; Benns, J.M., Choi, J.S., Mahato, R.I., Park, J.S., Kim, S.W., pH-sensitive cationic polymer gene delivery vehicle: N-Ac-poly(l-histidine)-graft-poly(l-lysine) comb shaped polymer (2000) Bioconjug Chem, 11, pp. 637-645; Putnam, D., Gentry, C.A., Pack, D.W., Langer, R., Polymer-based gene delivery with low cytotoxicity by a unique balance of side-chain termini (2001) Proc Natl Acad Sci USA, 98, pp. 1200-1205; Dubruel, P., Christiaens, B., Vanloo, B., Bracke, K., Rosseneu, M., Vandekerckhove, J., Physicochemical and biological evaluation of cationic polymethacrylates as vectors for gene delivery (2003) Eur J Pharm Sci, 18, pp. 211-220; Dubruel, P., Dekie, L., Schacht, E., Poly-l-glutamic acid derivatives as multifunctional vectors for gene delivery. Part A. Synthesis and physicochemical evaluation (2003) Biomacromolecules, 4, pp. 1168-1176; Kim, T.H., Ihm, J.E., Choi, Y.J., Nah, J.W., Cho, C.S., Efficient gene delivery by urocanic acid-modified chitosan (2003) J Control Release, 93, pp. 389-402; Dubruel, P., Christiaens, B., Rosseneu, M., Vandekerckhove, J., Grooten, J., Goossens, V., Buffering properties of cationic polymethacrylates are not the only key to successful gene delivery (2004) Biomacromolecules, 5, pp. 379-388; Juusola, P., Minkkinen, P., Leino, L., Laihia, J.K., Determination of the dissociation constants of urocanic acid isomers in aqueous solutions (2007) Monatsh Chem, 138, pp. 951-965; Roberts, J.D., Yu, C., Flanagan, C., Birdseye, T.R., A nitrogen-15 nuclear magnetic resonance study of the acid-base and tautomeric equilibria of 4-substituted imidazoles and its relevance to the catalytic mechanism of alfa-lytic protease (1982) J Am Chem Soc, 104, pp. 3945-3949; Roberts, G.A.F., (1992) Chitin chemistry, , Palgrave Macmillan, London; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Endotoxin contamination in wound dressings made of natural biomaterials (2003) J Biomed Mater Res B Appl Biomater, 66, pp. 347-355; (1987) Guideline on validation of the limulus amebocyte lysate test as an end-product endotoxin test for human and animal parenteral drugs, biological products, and medical devices, , U.S. Department of Health and Human Services, Public Health Service, Food and Drug Administration; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29, pp. 63-68; Sehgal, D., Vijay, I.K., A method for the high-efficiency of water-soluble carbodiimide-mediated amidation (1994) Anal Biochem, 218, pp. 87-91; Leong, K.W., Mao, H.Q., Truong-Le, V.L., Roy, K., Walsh, S.M., August, J.T., DNA-polycation nanospheres as non-viral gene delivery vehicles (1998) J Control Release, 53, pp. 183-193; Lee, M., Nah, J.W., Kwon, Y., Koh, J.J., Ko, K.S., Kim, S.W., Water-soluble and low molecular weight chitosan-based plasmid DNA delivery (2001) Pharm Res, 18, pp. 427-431; van Kuppeveld, F.J., van der Logt, J.T., Angulo, A.F., van Zoest, M.J., Quint, W.G., Niesters, H.G., Genus- and species-specific identification of mycoplasmas by 16S rRNA amplification (1992) Appl Environ Microbiol, 58, pp. 2606-2615; van Kuppeveld, F.J., van der Logt, J.T., Angulo, A.F., van Zoest, M.J., Quint, W.G., Niesters, H.G., Genus- and species-specific identification of mycoplasmas by 16S rRNA amplification (1993) Appl Environ Microbiol, 59, p. 655; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Godbey, W.T., Ku, K.K., Hirasaki, G.J., Mikos, A.G., Improved packing of poly(ethylenimine)/DNA complexes increases transfection efficiency (1999) Gene Ther, 6, pp. 1380-1388; Pouton, C.W., Lucas, P., Thomas, B.J., Uduehi, A.N., Milroy, D.A., Moss, S.H., Polycation-DNA complexes for gene delivery: a comparison of the biopharmaceutical properties of cationic polypeptides and cationic lipids (1998) J Control Release, 53, pp. 289-299; Mao, H.Q., Roy, K., Troung-Le, V.L., Janes, K.A., Lin, K.Y., Wang, Y., Chitosan-DNA nanoparticles as gene carriers: synthesis, characterization and transfection efficiency (2001) J Control Release, 70, pp. 399-421; Poole, B., Ohkuma, S., Effect of weak bases on the intralysosomal pH in mouse peritoneal-macrophages (1981) J Cell Biol, 90, pp. 665-669; Bowman, E.J., Siebers, A., Altendorf, K., Bafilomycins: a class of inhibitors of membrane ATPases from microorganisms, animal cells, and plant cells (1988) Proc Natl Acad Sci USA, 85, pp. 7972-7976; van Deurs, B., Holm, P.K., Sandvig, K., Inhibition of the vacuolar H+ATPase with bafilomycin reduces delivery of internalized molecules from mature multivesicular endosomes to lysosomes in HEp-2 cells (1996) Eur J Cell Biol, 69, pp. 343-350; Merdan, T., Kopecek, J., Kissel, T., Prospects for cationic polymers in gene and oligonucleotide therapy against cancer (2002) Adv Drug Deliv Rev, 54, pp. 715-758; Mansouri, S., Lavigne, P., Corsi, K., Benderdour, M., Beaumont, E., Fernandes, J.C., Chitosan-DNA nanoparticles as non-viral vectors in gene therapy: strategies to improve transfection efficacy (2004) Eur J Pharm Biopharm, 57, pp. 1-8; Erbacher, P., Zou, S.M., Bettinger, T., Steffan, A.M., Remy, J.S., Chitosan-based vector/DNA complexes for gene delivery: biophysical characteristics and transfection ability (1998) Pharm Res, 15, pp. 1332-1339; Kiang, T., Wen, J., Lim, H.W., Leong, K.W., The effect of the degree of chitosan deacetylation on the efficiency of gene transfection (2004) Biomaterials, 25, pp. 5293-5301; Ishii, T., Okahata, Y., Sato, T., Mechanism of cell transfection with plasmid/chitosan complexes (2001) BBA-Biomembranes, 1514, pp. 51-64; Lavertu, M., Methot, S., Tran-Khanh, N., Buschmann, M.D., High efficiency gene transfer using chitosan/DNA nanoparticles with specific combinations of molecular weight and degree of deacetylation (2006) Biomaterials, 27, pp. 4815-4824; de Smedt, S.C., Demeester, J., Hennink, W.E., Cationic polymer based gene delivery systems (2000) Pharm Res, 17, pp. 113-126; Kichler, A., Leborgne, C., Coeytaux, E., Danos, O., Polyethylenimine-mediated gene delivery: a mechanistic study (2001) J Gene Med, 3, pp. 135-144; Wattiaux, R., Laurent, N., Wattiaux-De Coninck, S., Jadot, M., Endosomes, lysosomes: their implication in gene transfer (2000) Adv Drug Deliv Rev, 41, pp. 201-208; Pelkmans, L., Helenius, A., Endocytosis via caveolae (2002) Traffic, 3, pp. 311-320; Felgner, P.L., Gadek, T.R., Holm, M., Roman, R., Chan, H.W., Wenz, M., Lipofection-a highly efficient, lipid-mediated DNA-transfection procedure (1987) Proc Natl Acad Sci USA, 84, pp. 7413-7417; Conner, S.D., Schmid, S.L., Regulated portals of entry into the cell (2003) Nature, 422, pp. 37-44; Koping-Hoggard, M., Tubulekas, I., Guan, H., Edwards, K., Nilsson, M., Varum, K.M., Chitosan as a nonviral gene delivery system. Structure-property relationships and characteristics compared with polyethylenimine in vitro and after lung administration in vivo (2001) Gene Ther, 8, pp. 1108-1121; Boussif, O., Zanta, M.A., Behr, J.P., Optimized galenics improve in vitro gene transfer with cationic molecules up to 1000-fold (1996) Gene Ther, 3, pp. 1074-1080
Keywords: article; beta galactosidase; Biocompatible Materials; Buffers; Cell Line; cell transport; Chemical structure; chitosan; coacervation; complex formation; controlled study; Cytotoxicity; Diffusion; DNA; Drug Carriers; Drug Compounding; endosome; Gene delivery; Gene transfer; genetic transfection; human; human cell; Humans; imidazole; Kidney; materials testing; nanomaterial; nanoparticle; priority journal; protein expression; proton transport; Tissue engineering; Transfection

In vitro biological characterization of macroporous 3D Bonelike ® structures prepared through a 3D machining technique - Laranjeira, M.S.; Dias, A.G.; Santos, J.D.; Fernandes, M.H. (Materials Science and Engineering CMater. Sci. Eng. C, 2009)
3D bioactive macroporous structures were prepared using a 3D machining technique. A virtual 3D structure model was created and a computer numerically controlled (CNC) milling device machined Bonelike ® samples. The resulting structures showed a reproducible macroporosity and interconnective structure. Macropores size after sintering was approximately 2000 μm. In vitro testing using human bone marrow stroma showed that cells were able to adhere and proliferate on 3D structures surface and migrate into all macropore channels. In addition, these cells were able to differentiate, since mineralized globular structures associated with cell layer were identified. Results obtained showed that 3D structures of Bonelike ® successfully allow cell migration into all macropores, and allow human bone marrow stromal cells to proliferate and differentiate. This innovative technique may be considered as a step-forward preparation for 3D interconnective macroporous structures that allow bone ingrowth while maintaining mechanical integrity. © 2008 Elsevier B.V. All rights reserved.
Keywords: 3-D structures; 3D machining techniques; Biological characterizations; Bone; Bone ingrowths; Bone marrow stroma cells; Bone substitute; Bonelike; Cell layers; Cell migrations; Computer control systems; cytology; Globular structures; Human bone marrow stromal cells; Human bone marrows; In-vitro; Machining; Macro porosities; Macro-pores; Macroporous; Macroporous structures; Mechanical integrities; Porous materials; Sintering; Surface testing; Three dimensional; ®

Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers - Gonçalves, R.M.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Notch signaling is a key mechanism during mammal development and stem cell regulation. This study aims to target and control Notch signaling by ligands immobilization using self-assembled monolayers (SAMs) as model surfaces. Non-fouling substrates were prepared by immersion of gold substrates in (1-Mercapto-11-undecyl)tetra(ethylene glycol) thiol solutions. These surfaces were activated with N,N′-carbonyldiimidazole (CDI) at different concentrations (0, 0.03, 0.3, 3 and 30 mg/ml) and an anti-human IgG, Fc specific fragment antibody (Ab) was covalently bound to EG4-SAMs to guarantee the correct exposure of the Notch ligand Jagged-1/Fc chimera (Jag-1). The presence of Ab and Jag-1 was confirmed by radiolabeling, X-ray photoelectron spectroscopy (XPS), ellipsometry and ELISA. The biological activity of Jag-1-Ab-SAMs was assessed by real-time PCR for Hes-1 family gene expression, a Notch pathway target gene, in HL-60 cell line. Results have shown an increase of the amount of immobilized Ab with increasing surface activator concentrations. Jag-1 concentration also increases with Ab concentration. Interestingly, a higher Jagged-1 exposure and fold increase in Hes-1 expression were obtained for surfaces activated with the lowest concentration of CDI (0.03 mg/ml). These results illustrate the great importance of ligands orientation and exposure, when compared with density. This investigation brings new insights into Notch signaling mechanisms. In particular, Jag-1-Ab-SAMs have shown to be adequate model surfaces to study Notch pathway activation and may provide a basis to develop new interfaces in biomaterials to control Notch mechanism in different cell systems. © 2009 Elsevier Ltd.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.09.010PubMed ID: 19783294Language of Original Document: EnglishCorrespondence Address: Gonçalves, R.M.; INEB, Biomaterials Division, NEWTherapies Group, R. Campo Alegre, 823, 4150-180 Porto, Portugal; email: raquelg@ineb.up.ptChemicals/CAS: Calcium-Binding Proteins; Gold, 7440-57-5; Immunoglobulin G; Intercellular Signaling Peptides and Proteins; Membrane Proteins; Receptors, Fc; Receptors, Notch; Recombinant Fusion Proteins; Serrate proteins, 134324-36-0References: Artavanis-Tsakonas, S., Rand, M.D., Lake, R.J., Notch signaling: cell fate control and signal integration in development (1999) Science, 284, pp. 770-776;Leong, K., Karsan, A., Recent insights in the role of notch signaling in tumorigenesis (2006) Blood, 107 (6), pp. 2223-2233; Chiba, S., Concise review: notch signaling in stem cell systems (2006) Stem Cells, 24, pp. 2437-2447; Lowell, S., Benchoua, A., Heavey, B., Smith, A.G., Notch promotes neural lineage entry by pluripotent embryonic stem cells (2006) PLoS Biol, 4 (5); Hellström, M.P.L., Hofmann, J.J., Wallgard, E., Coultas, L., Lindblom, P., Alva, J., Dll4 signalling through notch1 regulates formation of tip cells during angiogenesis (2007) Nature, 15 (445), pp. 776-780; Hofmeister, C., Zhang, J., Knight, K.L., Le, P., Stiff, P.J., Ex vivo expansion of umbilical cord blood stem cells for transplantation: growing knowledge from the hematopoietic niche (2007) Bone Marrow Transplant, 39 (1), pp. 11-23; Hilton, M., Tu, X., Wu, X., Bai, S., Zhao, H., Kobayashi, T., F. Notch signaling maintains bone marrow mesenchymal progenitors by suppressing osteoblast differentiation (2008) Nat Med, 14 (3), pp. 306-314; Stylianou, S., Clarke, R.B., Brennan, K., Aberrant activation of notch signaling in human breast cancer (2006) Cancer Res, 66 (3), pp. 1517-1525; Demarest, R., Ratti, F., Capobianco, A.J., It's T-ALL about notch (2008) Oncogene, 27 (38), pp. 5082-5091; Fre, S., Huyghe, M., Mourikis, P., Robine, S., Louvard, D., Artavanis-Tsakonas, S., Notch signals control the fate of immature progenitor cells in the intestine (2005) Nature, 16 (435), pp. 964-968; Fischer, A., Gessler, M., Delta-notch-and then? Protein interactions and proposed modes of repression by Hes and Hey bHLH factors (2007) Nucleic Acids Res, 35 (14), pp. 4583-4596; Zweidler-McKay, P.A., He, Y., Xu, L., Rodriguez, C.G., Karnell, F.G., Carpenter, A.C., Notch signaling is a potent inducer of growth arrest and apoptosis in a wide range of B-cell malignancies (2005) Blood, 106 (12), pp. 3898-3906; Beckstead, B., Santosa, D.M., Giachelli, C.M., Mimicking cell-cell interactions at the biomaterial-cell interface for control of stem cell differentiation (2006) J Biomed Mater Res, 79 A, pp. 94-103; Varnum-Finney, B., Wu, L., Yu, M., Brashem-Stein, C., Staats, S., Flowers, D., Immobilization of Notch ligand, Delta-1, is required for induction of notch signaling (2000) J Cell Sci, 113 (23), pp. 4313-4318; Delaney, C., Varnum-Finney, B., Aoyama, K., Brashem-Stein, C., Bernstein, I.D., Dose-dependent effects of the notch ligand delta1 on ex vivo differentiation and in vivo marrow repopulating ability of cord blood cells (2005) Blood, 106, pp. 2693-2699; Lefort, N., Bennea, C., Lelièvrea, J.D., Dorivala, C., Balboa, M., Sakanoc, S., Short exposure to notch ligand delta-4 is sufficient to induce T-cell differentiation program and to increase the T cell potential of primary human CD34+ cells (2006) Exp Hematol, 34, pp. 1720-1729; Taqvi, S., Dixit, L., Krishnendu, R., Biomaterial-based notch signaling for the differentiation of hematopoietic stem cells into T cells (2006) J Biomed Mater Res, 79 A, pp. 689-697; Bernstein, I., Delaney, C., Dallas, M., Heimfeld, S., Varnum-Finney, B., Notch signaling in hematopoiesis: implication for improving stem cell transplantation (2008) Biol Blood Marrow Transplant, 14, pp. 94-99; De Smedt, M., Hoebeke, I., Reyvoet, K., Leclercq, G., Plum, J., Different thresholds of Notch signaling bias human precursor cells toward B-, NK-, monocytic/dendritic-, or T-cell lineage in thymus microenvironment (2005) Blood, 106, pp. 3498-3506; Mrksich, M., What can surface chemistry do for cell biology? (2002) Curr Opin Chem Biol, 6, pp. 794-797; France, R., Short, R.D., Dawsonb, R.A., MacNeilb, S., Attachment of human keratinocytes to plasma copolymers of acrylic acid/octa-1,7-diene and allyl amine/octa-1,7-diene (1998) J Mater Chem, 81 (1), pp. 37-42; Neves, H., Weerkamp, F., Gomes, A.C., Naber, B., Gameiro, P., Becker, J.L., Effects of delta1 and jagged1 on early human hematopoiesis: correlation with expression of notch signaling-related genes in CD34+ Cells (2006) Stem Cells, 24, pp. 1328-1337; Sokolova, V., Epple, M., Inorganic nanoparticles as carriers of nucleic acids into cells (2008) Angewandte Chemie, 47, pp. 1382-1395; Yao, J., Duan, L., Fan, M., Yuan, J., Wu, X., Notch1 induces cell cycle arrest and apoptosis in human cervical cancer cells: involvement of nuclear factor kappa B inhibition (2007) Int J Gynecol Cancer, 17, pp. 502-510; Chadwick, N., Nostro, M.C., Baron, M., Mottram, R., Brady, G., Buckle, A., Notch signaling induces apoptosis in primary human CD34+ hematopoietic progenitor cells (2007) Stem Cells, 25, pp. 203-210; Love, J., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Martins, M.C.L., Ratner, B., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl- terminated self-assembled monolyers (2003) J Biomed Mater Res, 67 (A), pp. 158-171; Martins, M.C.L., Curtins, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88 (1), pp. 162-173; Barrias, C.C., Martins, M.C.L., Bidarra, S., Sá Miranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: effect of the surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; Iodine-125. A guide to radioiodination techniques. In: techniques I-Agtr, ed.: Little Chalfort: Amersham Life Science 1993Horbett, T., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, pp. 183-214. , DF W. (Ed), CRC Press Inc, Harcover; Ohishi, K., Varnum-Finney, B., Bernstein, I.D., Delta-1 enhances marrow and thymus repopulating ability of human CD34+ CD38- cord blood cells (2002) J Clin Invest, 110, pp. 1165-1174; Li, L., Chen, S., Zheng, J., Ratner, B.D., Jiang, S., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: the molecular basis for nonfouling behavior (2005) J Phys Chem B, 109 (7), pp. 2934-2941; Tohda, S., Murata-Ohsawa, M., Sakano, S., Nara, N., Notch ligands, Delta-1 and Delta-4 supress the self-renewal capacity and long-term growth of two myeloblastic leukemia cell lines (2003) Int J Oncol, 22 (5), pp. 1073-1079; Tohda, S.K.H., Murakami, N., Sakano, S., Nara, N., Diverse effects of the Notch ligands Jagged1 and Delta1 on the growth and differentiation of primary acute myeloblastic leukemia cells (2005) Exp Hematol, 33, pp. 558-563; Aoyama, K., Delaney, C., Varnun-Finney, B., Kohn, A.D., Moon, R.T., Bernstein, I.D., The interaction of the Wnt and notch pathways modulates natural killer versus T cell differentiation (2007) Stem Cells, 25, pp. 2488-2497; Beckstead B, Tung JC, Liang KJ, Tavakkol Z, Usui ML, Olerud JE, et al. Methods to promote notch signaling at the biomaterial interface and evaluation in a rafted organ culture model. J Biomed Mater Res A, in press. [Epub ahead of print]Semler, E., Dasgupta, A., Moghe, P.V., Cytomimetic engineering of hepatocyte morphogenesis and function by substrate-based presentation of acellular E-cadherin (2005) Tissue Eng, 11 (5-6), pp. 734-750; Zhao, Z., Matsui, H., Accurate immobilization of antibody-functionalized peptide nanotubes on protein-patterned arrays by optimizing their ligand-receptor interactions (2007) Small, 3 (8), pp. 1390-1393; Longo, G., Szleifer, Ligand-receptor interactions in tethered polymer layers (2005) Langmuir, 21, pp. 11342-11351; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption and clotting time of pHEMA hydrogels modified with C18 ligands to adsorb albumin selectively and reversibly (2009) Biomaterials, 30 (29), pp. 5541-5551
Keywords: Activator concentration; Adequate models; Adsorption; Animals; article; Bioactivity; Biological activities; Biological materials; biomaterial; Calcium-Binding Proteins; Carbonyldiimidazole; Cell culture; Cell Line; Cell membranes; cell strain HL 60; Cell system; Chemical activation; Concentration (process); Concentration of; controlled study; Covalently bound; Ethylene; Ethylene Glycol; gene expression; gold; Gold substrates; HL-60 cell line; human; human cell; Human IgG; Humans; Immunoassay; immunoglobulin Fc fragment; Immunoglobulin G; immunoglobulin G antibody; Intercellular Signaling Peptides and Proteins; Jagged1; Ligands; Mammalia; Membrane Proteins; Model surface; Molecular Structure; Nanostructured materials; Nanostructured surfaces; Nonfouling; Notch receptor; Notch signaling; Photoelectron spectroscopy; priority journal; Protein adsorption; protein immobilization; Radiolabeling; Real-time PCR; Receptors, Fc; Receptors, Notch; Recombinant Fusion Proteins; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; signal transduction; Signaling; stem cell; Surface Properties; Target genes; Tetra; transcription factor HES 1; X ray photoelectron spectroscopy

Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide - Martins, M.C.L.; Curtin, S.A.; Freitas, S.C.; Salgueiro, P.; Ratner, B.D.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2009)
Systemic heparinization, used during haemodialysis to prevent blood clotting on the extracorporeal circuit, leads to a high incidence of hemorrhagic complications. The adverse reactions associated with heparin neutralization using protamine sulphate justify the development of an alternative system for blood deheparinization. The main objective of this work is to design nanostructured surfaces with the capacity to bind heparin from blood in a selective way. A heparin-binding polypeptide, composed of L-lysine and L-leucine (pKL), was synthesized and immobilized, in different concentrations, onto self-assembled monolayers (SAMs) terminated with tetra(ethylene-glycol) (EG4 SAMs). Immobilization was performed using a fixed concentration of pKL after surface activation to different degrees using a range of CDI (N,N′-carbonyldiimidazole) concentrations. Results demonstrated that the presence of pKL increases heparin adsorption to EG4-SAMs, independently of the pKL concentration and the way of immobilization (adsorption or covalent bound). Selectivity towards heparin was successfully achieved on SAMs with low concentrations of immobilized pKL (9-17% of pKL). Surfaces were characterized using ellipsometry, contact angle measurements, Fourier transform infrared reflection absorption spectroscopy (IRAS), atomic force microscopy, and X-ray photoelectron spectroscopy. Heparin adsorption was assessed using IRAS and N-sulphonate- 35S-heparin. Therefore, this study could give a good contribution for the design of blood deheparinization devices. © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31849PubMed ID: 18286636Language of Original Document: EnglishCorrespondence Address: Martins, M. C. L.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomaterials, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180, Porto, Portugal; email: cmartins@ineb.up.ptChemicals/CAS: carbonyldiimidazole, 530-62-1; heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; imidazole, 1467-16-9, 288-32-4; leucine, 61-90-5, 7005-03-0; lysine, 56-87-1, 6899-06-5, 70-54-2; tetraethylene glycol, 112-60-7; Ethylene Glycol, 107-21-1; Heparin, 9005-49-6; Leucine, 61-90-5; Lysine, 56-87-1; PeptidesReferences: Dailey J. Blood. Ipswich, MA, USA: Medical Consulting Group; 1998Section, V., Chronic intermittent haemodialysis and prevention of clotting in the extracorporal system (2002) Nephrol Dialysis Transplant, 17, pp. 63-71;Zhang, Y.H., Singh, V.K., Yang, V.C., Novel approach for optimizing the capacity and efficacy of a protamine filter for clinical extracorporeal heparin removal (1998) Asaio J, 44, pp. M368-M373; Tao, W., Deyo, D.J., Brunston, R.L., Vertrees, R.A., Zwischenberger, J.B., Extracorporeal heparin adsorption following cardiopulmonary bypass with a heparin removal device - An alternative to protamine (1998) Critical Care Med, 26, pp. 1096-1102; Ameer, G.A., Barabino, G., Sasisekharan, R., Harmon, W., Cooney, C.L., Langer, R., Ex vivo evaluation of a Taylor-Couette flow, immobilized heparinase I device for clinical application (1999) Proc Natl Acad Sci USA, 96, pp. 2350-2355; Ostuni, E., Yan, L., Whitesides, G.M., The interaction of proteins and cells with self-assembled monolayers of alkanethiolates on gold and silver (1999) Colloids Surf B-Biointerfaces, 15, pp. 3-30; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers that present oligo(ethylene glycol) groups to control the interactions of proteins with surfaces. Poly(Ethylene Glycol) (1997) ACS Symposium Series, 680, pp. 361-373; Cardin, A.D., Weintraub, H.J.R., Molecular modeling of proteinglycosaminoglycan interactions (1989) Arteriosclerosis, 9, pp. 21-32; Kricheldorf, H.R., (1987) α-Amino Acid N-Carboxyanhydrides and Related Heterocycles, , New York: Springer Verlag;; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67, pp. 158-171; Lee, H.J., Nedelkov, D., Corn, R.M., Surface plasmon resonance imaging measurements of antibody arrays for the multiplexed detection of low molecular weight protein biomarkers (2006) Anal Chem, 78, pp. 6504-6510; Roeges, N.P.G., (1994) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , England: Wiley;; Li, L.Y., Chen, S.F., Zheng, J., Ratner, B.D., Jiang, S.Y., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: The molecular basis for non-fouling behavior (2005) J Phys Chem B, 109, pp. 2934-2941; Beamson, G., High, B.D., (1992) Resolution XPS of Organic Polymers, , Chichester: Wiley;; Sousa, S.R., Moradas, F.P., Saramago, B., Viseu, M.L., Barbosa, M.A., Human serum albumin adsorption on TiO2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Socrates, G., (2001) Infrared and Raman Characteristic Group Frequencies: Tables and Charts, , Chichester: Wiley;; Capila, I., Linhardt, R.J., Heparin - Protein interactions (2002) Angewandte Chemie-Int Ed, 41, pp. 391-112; Snell, C.R.F.G., Kinetics and thermodynamics of the alpha Helix - β Transconformation of poly(L-lysine) and L-leucine copolymers. A compensation phenomenon (1973) Biochemistry, 12, pp. 1017-1025; Hearn, M.T.W., 1,1′-Carbonyldiimidazole-mediated immobilization of enzymes and affinity ligands (1987) Methods Enzymol, 135, pp. 102-117; Stollner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1′-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304, pp. 157-165
Keywords: Absorption spectroscopy; Adsorption; Alternative systems; Amines; Amino acids; Angle measurement; article; Atomic force microscopy; Atomic forces; Atomic spectroscopy; Binding peptides; Blood; Blood clotting; Carbonyl diimidazole; Carbonyldiimidazole; Contact angle; deheparinization; device; Dialysis; Electron energy levels; ellipsometry; Ethylene; Ethylene Glycol; Fourier Transform Infrared; Fourier transforms; Glycols; Haemodialysis; heparin; heparin binding protein; Heparinization; High incidences; Humans; imidazole; immobilization; infrared spectroscopy; leucine; Low concentrations; lysine; Methods; Missile bases; Monolayers; nanomaterial; Nanostructured surfaces; Nanostructures; Peptide immobilization; Peptides; Photoelectron spectroscopy; Polysaccharides; Protein adsorption; protein binding; Renal Dialysis; Self assembled monolayers; Self-assembled monolayers; Sulphate; Surface activations; Surface functionalization; Surface Properties; surface property; tetraethylene glycol; unclassified drug; X ray photoelectron spectroscopy; X-ray photoelectron spectroscopies

Morphology and mechanical properties of injectable ceramic microspheres - Oliveira, S.M.; Barrias, C.C.; Ribeiro, C.C.; Almeida, I.F.; Bahia, M.F.; Barbosa, M.A. (Key Engineering MaterialsKey Eng Mat, 2009)
The aim of this study was to analyze the effect of starting powder granulometry and sintering conditions on the morphological structure and mechanical properties of injectable hydroxyapaptite (HAp) microspheres. The mechanical properties of the microspheres were evaluated, to investigate if their integrity could be maintained during the injection process. To obtain microspheres, HAp powders were dispersed in a sodium alginate solution and spherical particles were prepared by droplet extrusion under a co-axial air stream, coupled with ionotropic gelation in the presence of Ca 2+. This was followed by a sintering process at various temperatures and times. The morphology of microspheres was observed under SEM, diameter measurements were performed in an optical microscope and the compression strength was evaluated using a texture analyzer. Finally, microspheres prepared using lower granulometry HAp powders and sintered at 1200°C for 1 hour presented the best properties and were selected as the most suitable for the envisaged application.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAEdoi: 10.4028/0-87849-353-0.691Language of Original Document: EnglishCorrespondence Address: Oliveira, S. M.; ESTV, Departamento de Engenharia Mecânica, Instituto Politécnico de Viseu, Viseu, PortugalReferences: Barrias, C.C., Ribeiro, C.C., Lamghari, M., Miranda, C.S., Barbosa, M.A., Proliferation, activity, and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) Journal of Biomedical Materials Research, 72 A (1), pp. 57-66;Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Bioceramics, 16, pp. 254-262,877-880; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25 (18), pp. 4363-4373; Silva, R.V., Camilli, J.A., Bertran, C.A., Moreira, N.H., The use of hydroxyapatite and autogenous cancellous bone grafts to repair bone defects in rats (2005) International Journal of Oral and Maxillofacial Surgery, 34 (2), pp. 178-184; Boyan, B.D., Lossdörfer, S., Wang, L., Zhao, G., Lohmann, C.H., Cochran, D.L., Schwartz, Z., Osteoblasts generate an osteogenic microenvironment when grown on surfaces with rough microtopographies (2003) Eur Cell Mater, 6, pp. 22-27; Cardoso, O.N., Sotto Mayor, T., Pinto, A.M.F.R., Campos, J.B.L.M., Axial dispersion of particles in a slugging column - the role of the laminar wake of the bubbles (2003) Chemical Engineering Science, 58 (18), pp. 4159-4172; Gauthier, O., Bouler, J.M., Weiss, P., Bosco, J., Aguado, E., Daculsi, G., Short-term effects of mineral particle sizes on cellular degradation activity after implantation of injectable calcium phosphate biomateriais and the consequences for bone substitution (1999) Bone, 25 (2), pp. 71S-74S; Xu, H.H., Weir, M.D., Burguera, E.F., Fraser, A.M., Injectable and macroporous calcium phosphate cement scaffold (2006) Biomaterials, 27 (24), pp. 4279-4287; Ginebra, M.P., Rilliard, A., Fernandez, E., Elvira, C., San Roman, J., Planell, J.A., Mechanical and rheological improvement of a calcium phosphate cement by the addition of a polymeric drug (2001) J Biomed Mater Res, 57 (1), pp. 113-118
Keywords: Air streams; Apatite; Calcium; Ceramic microspheres; Co-axial; Coagulation; Compression strengths; Diameter measurements; Gelation; Granulometry; hydroxyapatite; Injectable; Injection process; Ionotropic gelations; Mechanical properties; Microspheres; Morphological structures; Morphology and mechanical properties; Optical microscopes; Powders; SEM; Sintering; Sintering conditions; Sintering process; Sodium; Sodium alginates; Spherical particles; Starting powders; Texture analyzers

Neural cell growth on TiO 2 anatase nanostructured surfaces - Collazos-Castro, J.E.; Cruz, A.M.; Carballo-Vila, M.; Lira-Cantú, M.; Abad, L.; del Pino, Á.P.; Fraxedas, J.; San Juan, A.; Fonseca, C.; Pêgo, A.P.; Casañ-Pastor, N. (Thin Solid FilmsThin Solid Films, 2009)
Titanium oxides have anti-inflammatory activity and tunable electrochemical properties that make them attractive materials for biomedical applications. This work investigated the compatibility of nanometric coatings of low-temperature phases of TiO 2 with neurons in 4-day and 10-day cultures, using different cell densities to quantify cell survival and neurite extension. TiO 2 films were prepared by sol-gel and thermal treatment (250-450 °C) of hydrolyzed titanium tetra-isopropoxide on electrically conducting or insulating slides. The conducting substrates were not passivated by the nanometric oxide layer and could be used as electrodes. Characterization of the films showed nano-structured TiO 2 containing exclusively Ti +4 valence in anatase and amorphous phases. When coated with polylysine, all films permitted good neuron attachment and survival for at least ten days in culture. However, they generally reduced neurite growth compared to cell culture borosilicate glass, with dendrites more affected than axons. The analyses of surface topography, hydrophilicity, charge and chemical composition revealed that TiO 2 chemistry was the main factor responsible for neurite inhibition. © 2009 Elsevier B.V. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2009.06.048Language of Original Document: EnglishCorrespondence Address: Casañ-Pastor, N.; Instituto de Ciencias de Materiales de Barcelona, CSIC, Campus la Universidad Autonoma Barcelona, E-08193 Barcelona, Spain; email: nieves@icmab.esReferences: Suzuki, R., Frangos, J.Á., (2000) Clin. Orthop. Relat. Res., 372, p. 280;Suzuki, R., Muyco, J., McKittrick, J., Frangos, J.A., (2003) J. Biomed. Mater. Res. A, 66, p. 396; Ulbrich, M.H., Fromherz, P., (2005) Appl. Phys. A., 81, p. 887; Topoglidis, E., Lutz, T., Willis, R.L., Barnett, C.J., Cass, A.E., Durrant, J.R., (2000) Faraday Discuss., 116, p. 35; Smith, J.R., Walsh, F.C., Clarke, R.L., (1998) J. Appl. Electrochem., 28, p. 1021; Dinh, N.N., Oan, N.T., Long, P.D., Bernard, M.N., Hugot-Le Goffb, A., (2003) Thin Solid Films, 423, p. 70; (2001) Titanium in Medicine, , Brunette D.M., Tengvall P., Textor M., and Thomsen P. (Eds), Springer-Verlag, Berlin; Textor, M., Sittig, C., Frauchiger, V., Tosatti, S., Brunette, D.M., (2001) Titanium in Medicine, 171. , Brunette D.M., Tengvall P., Textor M., and Thomsen P. (Eds), Springer-Verlag, Berlin; Contreras, R., Sahlin, H., Frangos, J.Á., (2007) J. Biomed. Mater. Res. A, 80, p. 480; Kolbrecka, K., Przyluski, J., (1994) Electrochim. Acta, 39, p. 1591; Diebold, U., (2003) Surf. Sci. Rep., 48, p. 53; Jeong, B.S., Norton, D.P., Budai, J.D., (2003) Solid-State Electron., 47, p. 2275; Moulton, S.E., Barisci, J.N., Bath, A., Stella, R., Wallace, G.C., (2005) Langmuir, 21, p. 316; Jackson, D.R., Omanovic, S., Roscoe, S.G., (2005) Langmuir, 16, p. 5449; Subramanian, V., Karki, A., Gnanasekar, K.I., Eddy, FP., Rambabu, B., (2006) J. Power Sources, 159, p. 186; Carballo-Vila, M., Moreno-Burriel, B., Jurado, J.R., Chinarro, E., Casañ-Pastor, N., Collazos-Castro, J.E., (2009) J. Biomed. Mater. Res. A, 90, p. 94; Brewer, G.J., Torricelli, J.R., Evege, E.K., Price, P.J., (1993) J. Neurosci. Res., 35, p. 567; Rajnicek, A.M., Britland, S., McCaig, C.D., (1997) J. Cell Sci., 110, p. 2905; Bao, W., Thullberg, M., Zhang, H., Onischenko, A., Strömblad, S., (2002) Mol. Cell. Biol., 22, p. 4587; Sanjana, N.E., Fuller, S.B., (2004) J. Neurosci. Methods, 136, p. 151; Parak, W.J., George, M., Kudera, M., Gaub, H.E., Behrends, J.C., (2001) Eur. Biophys. J., 29, p. 607; Dotti, C.G., Sullivan, C.A., Banker, G.A., (1988) J. Neurosci., 8, p. 1454; Davenport, R.W., McCaig, C.D., (1993) J. Neurobiology, 24, p. 89; Chuckowree, J.A., Vickers, J.C., (2003) J. Neurosci., 23, p. 3715; Long, T.C., Saleh, N., Tilton, R.D., Lowry, G.V., Veronesi, B., (2006) Environ. Sci. Technol., 40, p. 4346; Zhao, L., Chang, J., Zhai, W., (2005) J. Biomater. Appl., 19, p. 237; Swamy, V., Kusnetzov, A., Dubrovinsky, L.S., Caruso, R.A., Shchukin, D.G., Muddle, B.C., (2005) Phys. Rev., B, 71, p. 1; Lozano, M.P., Fraxedas, J., (2000) Surf. Interface Anal., 30, p. 623; Martínez-Ferrero, E., Sakatani, Y., Boissière, C., David Grosso, D., Fuertes, A., Fraxedas, J., Sánchez, C., (2007) Adv. Funct. Mater., 17, p. 3348; Roddick-Lanzilotta, A.D., McQuillan, A.J., (1999) J. Colloid Interface Sci., 217, p. 194; Kosmulski, M., (2002) Adv. Colloid Interface Sci., 99, p. 255; Ikegaya, Y., Itsukaichi-Nishida, Y., Ishihara, M., Tanaka, D., Matsuki, N., (2000) Neuroscience, 97, p. 215; Cyster, L.A., Parker, K.G., Parker, T.L., Grant, D.M., (2004) Biomaterials, 25, p. 97; Blau, A., Weinl, C., Mack, J., Kienle, S., Jung, G., Ziegler, C., (2001) J. Neurosci. Methods, 112, p. 65; Kommireddy, D.S., Sriram, S.M., Lvov, Y.M., Mills, D.K., (2006) Biomaterials, 27, p. 4296; Cai, K., Bossert, J., Jandt, K.D., (2006) Colloids Surf., B, 49, p. 136; Wang, Y.-X., Robertson, J.L., Spillman Jr., W.B., Claus, R.O., (2004) Pharm. Res., 21, p. 1362; Greve, F., Frerker, S., Bittermann, A.G., Burkhardt, C., Hierlemann, A., Hall, H., (2007) Biomaterials, 28, p. 5246; Yang, H., Fung, S.-Y., Pritzker, M., Chen, P., (2007) PLoS ONE, 2, pp. e1325; Giovambattista, N., Debenedetti, P.G., Rosky, P.J., (2007) J. Phys. Chem. B, 111, p. 9581; Onur, M.A., Taş, Z., Gürpnar, A., Şahin, A., Çehreli, M.C., (2004) Clin. Oral Implants Res., 15, p. 513; Lopez, T., Ortiz-Islas, E., Manjarrez, J., Rodríguez-Reinoso, F., Sepúlveda, A., Gonzalez, R.D., (2006) Opt. Mater., 29, p. 70
Keywords: Amorphous phasis; Anatase; Anti-inflammatory activity; Biomedical applications; Borosilicate glass; Cell culture; cell density; Cell membranes; cell survival; Chemical compositions; Coatings; Conducting substrates; Conductive films; Electrochemical properties; Gelation; Growth kinetics; Heat treatment; Iso-propoxide; Low temperature phasis; Nano-structured; Nanometrics; Nanostructured surface; Nanostructures; Neural cell; Neural cells; Neurite extension; Neurite growth; Neurites; Neurons; Oxide layer; polylysine; Surface topography; Thermal treatment; TiO; Titanium; Titanium dioxide; Titanium oxide; Titanium oxides

A new method for the detection of singular points in fingerprint images - Magalhães, F.; Oliveira, H.P.; Campilho, A.C. (2009 Workshop on Applications of Computer Vision, WACV 2009Workshop Appl. Comput. Vis., WACV, 2009)
Automatic biometric identification based on fingerprints is still one of the most reliable identification method in criminal and forensic applications. A critical step in fingerprint analysis without human intervention is to automatically and reliably extract singular points from the input fingerprint images. These singular points (cores and deltas) not only represent the characteristics of local ridge patterns but also determine the topological structure (i.e., fingerprint type) and largely influence the orientation field. Poincaré Index-based methods are one of the most common for singular points detection. However, these methods usually result in many spurious detections. Therefore, we propose an enhanced version of the method presented by Zhou et al. [13] that introduced a feature called DORIC to improve the detection. Our principal contribution lies in the adoption of a smoothed orientation field and in the formulation of a new algorithm to analyze the DORIC feature. Experimental results show that the proposed algorithm is accurate and robust, giving better results than the best reported results so far, with improvements in the range of 5% to 7%. © 2009 IEEE.
Conference code: 79821Export Date: 21 November 2012Source: ScopusArt. No.: 5403106doi: 10.1109/WACV.2009.5403106Language of Original Document: EnglishCorrespondence Address: Magalhães, F.; INESC, Porto, Portugal; email: filipe.magalhaes@inescporto.ptReferences: Drets, G.A., Liljenström, H.G., (1999) Intelligent Biometric Techniques in Fingerprint and Face Recognition, , CRC Press, New York;Hong, L., Wan, Y., Fingerprint image enhancement: Algorithm and performance evaluation (1998) IEEE Transactions On, Pattern Analysis and Machine Intelligence, 20 (8), pp. 777-789; Jain, A., Hong, L., Bolle, R., On-line fingerprint verification (1997) IEEE Transactions on Pattern Analysis and Machine Intelligence, 19 (4), pp. 302-314; Jinwei, G., Jie, Z., A novel model for orientation field of fingerprints (2003) Proceedings IEEE Computer Society Conference on Computer Vision and Pattern Recognition, 2, pp. II493-II498; Kara, K., Jain, A.K., Fingerprint classification (1996) Pattern Recognition, 29 (3), pp. 389-404; Kass, M., Witkin, A., Analyzing oriented patterns (1987) Cornput. Vision Graph. Image Process, 37 (3), pp. 362-385. , 27996; Kawagoe, M., Tojo, A., Fingerprint pattern classification (1984) Pattern Recognition, 17 (3), pp. 295-303; Maio, D., Maltoni, D., Cappelli, R., Wayman, J.L., Jain, A.K., FVC2002: Second fingerprint verification competition (2002) Proceedings - International Conference on Pattern Recognition, 16 (3), pp. 811-814; Maio, D., Maltoni, D., Cappelli, R., Wayman, J.L., Jain, A.K., Fvc2004: Third fingerprint verification competition (2004) Proceedings International Conference on Biometric Authentication (ICBA), pp. 1-7. , Hong Kong; Pankanti, S., Prabhakar, S., Jain, A.K., On the individuality of fingerprints (2002) IEEE Transactions on Pattern Analysis and Machine Intelligence, 24 (8), pp. 1010-1025; Sherlock, B.G., Monro, D.M., A model for interpreting fingerprint topology (1993) Pattern Recognition, 26 (7), pp. 1047-1055; Srinivasan, V.S., Murthy, N.N., Detection of singular points in fingerprint images (1992) Pattern Recognition, 25 (2), pp. 139-153; Zhou, J., Chen, F., Gu, J., A novel algorithm for detecting singular points from fingerprint images (2009) IEEE Transactions on Pattern Analysis and Machine Intelligence, 31 (7), pp. 1239-1250
Keywords: Algorithms; Biometric identifications; Biometrics; Computer applications; Computer vision; Critical steps; Fingerprint analysis; Fingerprint images; Forensic applications; Human intervention; Identification method; Orientation fields; Poincare; Ridge patterns; Singular points; Structural optimization; Technical presentations; Topological structure

NPY revealed as a critical modulator of osteoblast function in vitro: New insights into the role of Y1 and Y2 receptors - Teixeira, L.; Sousa, D.M.; Nunes, A.F.; Sousa, M.M.; Herzog, H.; Lamghari, M. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2009)
Neuropeptide Y (NPY) has recently emerged as a potential regulator of bone homeostasis. However, the relevance of NPY's role in osteoblast activity and the biological functions involving NPY receptors in bone homeostasis remain to be clarified. Here we report that chronically elevated NPY levels leaded to a modulation of the level of Y2 receptor expression marked with a transient down and upregulation according to the stage of osteoblast differentiation. We also show that NPY is a negative regulator of Y1 receptor expression. The pharmalogical activation of Y2 receptor with its agonist resulted in similar effect. Functional analysis also revealed the osteogenic potential of NPY with osteoblast phenotype markers being significantly enhanced in osteoprogenitor cells stimulated by NPY, probably due to the down-regulation of Y1 receptor. In contrasts, these cells exhibit a reduction in calcium deposition in extracellular matrix most likely mediated via Y2 receptor signalling. Furthermore, we show that NPY modulates receptor activator of nuclear factor kB (NF-kB) (RANK) ligand and osteoprotegerin, two key factors regulating bone remodelling. Specifically, NPY inhibits the transcriptional activity of RANKL promoter in osteoprogenitor cells and enhances OPG expression in osteoblasts at early stages of differentiation. However, NPY effect on OPG seemed to be unrelated to Y2 receptor activation. Taken together the present data supported the contribution of NPY pathway in bone homeostasis via a direct action on osteoblasts cells. © 2009 Wiley-Liss, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.22194PubMed ID: 19459152Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; Instituto de Engenharia Biomédica (INEB), Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: calcium, 14092-94-5, 7440-70-2; osteoclast differentiation factor, 200145-93-3; osteoprotegerin, 205944-50-9; Alkaline Phosphatase, 3.1.3.1; Neuropeptide Y; Osteoprotegerin; RANK Ligand; Receptors, Neuropeptide YReferences: Ahmed, M., Srinivasan, G.R., Theodorsson, E., Bjurholm, A., Kreicbergs, A., Extraction and quantitation of neuropeptides in bone by radioimmunoassay (1994) Regul Pept, 51, pp. 179-188;Allison, S.J., Herzog, H., NPY and bone (2006) EXS, 95, pp. 171-182; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugman, M., Gardiner, E.M., Conditional deletion of hypothalamic Y2 receptors reverts gonadectomy-induced bone loss in adult mice (2006) J Biol Chem, 281, pp. 23436-23444; Amano, S., Arai, M., Goto, S., Togari, A., Inhibitory effect of NPY on isoprenaline-induced osteoclastogenesis in mouse bone marrow cells (2007) Biochim Biophys Acta, 1770, pp. 966-973; Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Ghomas, G.P., Gardiner, E.M., Herzog, H., Hypothalamic Y2 receptors regulate bone formation (2002) J Clin Investig, 109, pp. 915-921; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., Hypothalamic control of bone formation: Distinct actions of leptin and y2 receptor pathways (2005) J Bone Miner Res, 20, pp. 1851-1857; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., Herzog, H., Novel role of Y1 receptors in the coordinated regulation of bone and energy homeostasis (2007) J Biol Chem, 282, pp. 19092-19102; Chenu, C., Role of innervation in the control of bone remodelling (2004) J Musculoskel Neuron Interact, 4, pp. 132-134; Chenu, C., Marenzana, M., Sympathetic nervous system and bone remodeling (2005) Joint Bone Spine, 72, pp. 481-483; Clark, J.T., Kalra, P.S., Kalra, S.P., Neuropeptide Y stimulates feeding but inhibits sexual behavior in rats (1985) Endocrinology, 117, pp. 2435-2442; Dumont, Y., Jacques, D., Bouchard, P., Quirion, R., Species differences in the expression and distribution of the neuropeptide Y Y1, Y2, Y4, and Y5 receptors in rodents, guinea pig, and primates brains (1998) J Comp Neurol, 402, pp. 372-384; Elefteriou, F., Neuronal signalling and the regulation of bone remodelling (2005) Cell Mol Life Sci, 62, pp. 2339-2349; Ericsson, A., Schalling, M., McIntyre, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., Detection of neuropeptide Y and its mRNA in megakaryocytes: Enhanced levels in certain autoimmune mice (1987) Proc Natl Acad Sci USA, 84, pp. 5585-5589; Fu, Q., Manolagas, S.C., O'Brien, C.A., Parathyroid hormone controls receptor activator of NF-kappaB ligand gene expression via a distant transcriptional enhancer (2006) Mol Cell Biol, 26, pp. 6453-6468; Gori, F., Hofbauer, L.C., Dunstan, C.R., Spelsberg, T.C., Khosla, S., Riggs, B.L., The expression of osteoprotegerin and RANK ligand and the support of osteoclast formation by stromal-osteoblast lineage cells is developmentally regulated (2000) Endocrinology, 141, pp. 4768-4776; Herzog, H., Neuropeptide Y and energy homeostasis: Insights from Y receptor knockout models (2003) Eur J Pharmacol, 480 (1-3), pp. 21-29; Hill, E.L., Turner, R., Elde, R., Effects of neonatal sympathectomy and capsaicin treatment on bone remodeling in rats (1991) Neuroscience, 44 (3), pp. 747-755; Holliday, N.D., Michel, M.C., Cox, H.M., NPY receptor subtypes and their signal transduction (2004) Neuropeptide Y and related peptides, Handbook of experimental pharmacology, 162, pp. 45-74. , Michel MC, editor, Berlin: Springer-Verlag, Heidelberg, pp; Hosaka, H., Nagata, A., Yoshida, T., Shibata, T., Nagao, T., Tanaka, T., Saito, Y., Tatsuno, I., Pancreatic polypeptide is secreted from and controls differentiation through its specific receptors in osteoblastic MC3T3-E1 cells (2008) Peptides, 29 (8), pp. 1390-1395; Imai, S., Matsusue, Y., Neuronal regulation of bone metabolism and anabolism: Calcitonin gene-related peptide-, substance P-, and tyrosine hydroxylase-containing nerves and the bone (2002) Microsc Res Tech, 58, pp. 61-69; Kondo, H., Guo, J., Bringhurst, F.R., Cyclic adenosine monophosphate/protein kinase A mediates parathyroid hormone/parathyroid hormone-related protein receptor regulation of osteoclastogenesis and expression of RANKL and osteoprotegerin mRNAs by marrow stromal cells (2002) J Bone Miner Res, 17, pp. 1667-1679; Kuo, L.E., Kitlinska, J.B., Tilan, J.U., Li, L., Baker, S.B., Johnson, M.D., Lee, E.W., Zukowska, Z., Neuropeptide Y acts directly in the periphery on fat tissue and mediates stress-induced obesity and metabolic syndrome (2007) Nat Med, 13, pp. 803-811; Lee, S.K., Lornezo, J.A., Regulation of receptor activator of nuclear factor-kappaB ligand and osteoprotegerin mRNA expression by parathyroid hormone is predominantly mediated by the protein kinase a pathway in murine bone marrow cultures (2002) Bone, 31, pp. 252-259; Lerner, U.H., Lundberg, P., Kinins, neuro-osteogenic factors (2002) Principles of bone biology, pp. 773-799. , Bilezikian JP, Raisz LG, Rodan GA, editors, 2nd edition. San Diego: Academic Press. pp; Li, J., Ahmad, T., Spetea, M., Ahmed, M., Kreicbergs, A., Bone reinnervation after fracture: A study in the rat (2001) J Bone Miner Res, 16, pp. 1505-1510; Lundberg, P., Lerner, U.H., Expression and regulatory role of receptors for vasoactive intestinal peptide in bone cells (2002) Microsc Res Tech, 58, pp. 98-103; Lundberg, P., Boström, I., Mukohyama, H., Bjurholm, A., Smans, K., Lerner, U.H., Neuro-hormonal control of bone metabolism: Vasoactive intestinal peptide stimulates alkaline phosphatase activity and mRNA expression in mouse calvarial osteoblasts as well as calcium accumulation mineralized bone nodules (1999) Regul Pept, 85, pp. 47-58; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Herzog, H., Greater bone formation of Y2 knockout mice is associated with increased osteoprogenitor numbers and altered Y1 receptor expression (2007) J Biol Chem, 282, pp. 19082-19091; Michel, M.C., Beck-Sickinger, A., Cox, H., Doods, H.N., Herzog, H., Larhammar, D., Quirion, R., Westfall, T., XVI. International Union of Pharmacology recommendations for the nomenclature of neuropeptide Y, peptide YY, and pancreatic polypeptide receptors (1998) Pharmacol Rev, 50, pp. 143-150; Movafagh, S., Hobson, J.P., Spiegel, S., Kleinman, H.K., Zukowska, Z., Neuropeptide Y induces migration, proliferation, and tube formation of endothelial cells bimodallyvia Y1, Y2, and Y5 receptors (2006) FASEB J, 20, pp. 1327-1337; Sainsbury, A., Baldock, P.A., Schwarzer, C., Ueno, N., Enriquez, R.F., Couzens, M., Inui, A., Gardiner, E.M., Synergistic effects of Y2 and Y4 receptors on adiposity and bone mass revealed in double knockout mice (2003) Mol Cell Biol, 23, pp. 5225-5233; Serre, C.M., Farlay, D., Delmas, P.D., Chenu, C., Evidence for a dense and intimate innervation of the bone tissue, including glutamate-containing fibers (1999) Bone, 25, pp. 623-629; Simonet, W.S., Lacey, D.L., Dunstan, C.R., Kelley, M., Chang, M.S., Lüthy, R., Nguyen, H.Q., Boyle, W.J., Osteoprotegerin: A novel secreted protein involved in the regulation of bone density (1997) Cell, 89, pp. 309-319; Sudo, H., Kodama, H.A., Amagai, Y., Yamamoto, S., Kasai, S., In vitro differentiation and calcification in a new clonal osteogenic cell line derived from newborn mouse calvaria (1983) J Cell Biol, 96, pp. 191-198; Szczesny, G., Molecular aspects of bone healing, remodelling (2002) Pol J Pathol, 53, pp. 145-153; Tatemoto, K., Neuropeptide Y: Complete amino acid sequence of the brain peptide (1982) Proc Natl Acad Sci USA, 79, pp. 5485-5489; Thiriet, N., Deng, X., Solinas, M., Ladenheim, B., Curtis, W., Goldberg, S.R., Palmiter, R.D., Cadet, J.L., Neuropeptide Y protects against methamphetamine-induced neuronal apoptosis in the mouse striatum (2005) J Neurosci, 25, pp. 5273-5279; Wittmann, W., Loacker, S., Kapeller, I., Herzog, H., Schwarzer, C., Y1-receptors regulate the expression of Y2-receptors in distinct mouse forebrain areas (2005) Neuroscience, 136, pp. 241-250; Wortley, K.E., Garcia, K., Okamoto, H., Thabet, K., Anderson, K.D., Shen, V., Herman, J.P., Sleeman, M.W., Peptide YY regulates bone turnover in rodents (2007) Gastroenterology, 133, pp. 1534-1543
Keywords: alkaline phosphatase; animal cell; animal tissue; Animals; article; Bone; Bone Marrow Cells; bone remodeling; Calcium; cell activity; cell differentiation; cell function; Cell Line; cell stimulation; controlled study; down regulation; extracellular matrix; gene expression regulation; genetic transcription; Homeostasis; immunoglobulin enhancer binding protein; in vitro study; Mice; neuropeptide Y; neuropeptide Y1 receptor; neuropeptide Y2 receptor; nonhuman; NPY; nuclear factor Y; osteoblast; Osteoblasts; osteoclast differentiation factor; Osteoprotegerin; phenotype; priority journal; promoter region; protein expression; RANK Ligand; Receptors, Neuropeptide Y; Reverse Transcriptase Polymerase Chain Reaction; signal transduction; stem cell; Stromal Cells; upregulation; Y1 receptor; Y2 receptor

NPY signalling pathway in bone homeostasis: Y1 receptor as a potential drug target - Sousa, D.M.; Herzog, H.; Lamghari, M. (Current Drug TargetsCurr. Drug Targets, 2009)
Neuropeptide (NPY) is a neurotransmitter widely distributed in central and peripheral nervous system that has been implicated in several physiological processes through activation of five different Y receptors: Y1, Y2, Y4, Y5, and y6. NPY system has been extensively studied for the last decades due to its implications in a wide variety of physiological processes. For this purpose a diversity of sophisticated animal models and receptors agonists and antagonists has been developed to better understand its actions throughout body homeostasis. Consequently, NPY and its receptors have recently emerged as a potential regulator of bone homeostasis. This is supported by the demonstration of an increase of bone mass in mice lacking Y1 or Y2 receptor genes. Recent findings revealed Y1 receptor as a potential drug target candidate for prevention and treatment of bone loss. Indeed, it has been demonstrated that osteoblasts express Y1 receptor while no other Y receptor was detected in these cells, implicating Y1 receptor signalling in the local control of bone turnover. In this review, we have summarized the findings obtained from studies on NPY system in skeletogenesis focusing on Y1 receptor. © 2009 Bentham Science Publishers Ltd.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: CDTUAdoi: 10.2174/138945009787122888Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB - Instituto de Engenharia Biomédica, Universidade do Porto, NEWTherapies Group, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: gr 231118, 158859-98-4; n [1 [4 [[[[4 [(dimethylamino)methyl]cyclohexyl]methyl]amino]iminomethyl]benzyl] 2 oxo 2 (1 pyrrolidinyl)ethyl] alpha [(2 naphthalenylsulfonyl)amino]benzenepropanamide, 163238-19-5; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide, 191868-14-1, 217977-06-5; nalpha (diphenylacetyl) n (4 hydroxybenzyl) dextro argininamide, 159013-54-4; neuropeptide Y, 82785-45-3, 83589-17-7; peptide YY, 81858-94-8; Ligands; Neuropeptide Y; Receptors, Neuropeptide YTradenames: bibo 3304; bibp 3226; gi 264879a; gr 231118; gw 1229; j 115814; ly 357897; sr 120819aReferences: Lundberg, P., Lerner, U.H., (2002) Microsc. Res. Tech, 58 (2), pp. 98-103;Baldock, P.A., Sainsbury, A., Couzens, M., Enriquez, R.F., Thomas, G.P., Gardiner, E.M., Herzog, H., (2002) J. Clin. Invest, 109 (7), pp. 915-921; Baldock, P.A., Allison, S., McDonald, M.M., Sainsbury, A., Enriquez, R.F., Little, D.G., Eisman, J.A., Herzog, H., (2006) J. Bone Miner. Res, 21 (10), pp. 1600-1607; Tatemoto, K., Carlquist, M., Mutt, V., (1982) Nature, 296 (5858), pp. 659-660; Tatemoto, K., (1982) Proc. Natl. Acad. Sci. U.S.A, 79 (18), pp. 5485-5489; Larhammar, D., (1996) Regul. Pept, 62, pp. 1-11; Tatemoto, K., (1982) Proc. Natl. Acad. Sci. U.S.A, 79 (8), pp. 2514-2518; Kimmel, J.R., Hayden, J., Pollock, H.G., (1975) J. Biol. Chem, 250 (24), pp. 9369-9376; Michel, M.C., Beck-Sickinger, A., Cox, H., Doods, H.N., Herzog, H., Larhammar, D., Quirion, R., Westfall, T., (1998) Pharmacol. Rev, 50 (1), pp. 143-150; Fuhlendorff, J., Johansen, N.L., Melberg, S.G., Thogersen, H., And Schwartz, T.W., (1990) J. Biol. Chem, 265 (20), pp. 11706-11712; Blundell, T.L., Pitts, J.E., Tickle, I.J., Wood, S.P., Wu, C.W., (1981) Proc. Natl. Acad. Sci. U.S.A, 78 (7), pp. 4175-4179; Cerdá-Reverter, J., Larhammar, D., (2000) Biochem. Cell Biol, 78 (3), pp. 371-392; Allen, J., Novotný, J., Martin, J., Heinrich, G., (1987) Proc. Natl. Acad. Sci. U.S A, 84 (8), pp. 2532-2536; Wan, C.P., Lau, B.H.S., (1995) Life Sci, 56 (13), pp. 1055-1064; Schwartz, T.W., Fuhlendorff, J., Kjems, L.L., Kristensen, M.S., Vervelde, M., O'Hare, M., Krstenansky, J.L., Bjornholm, B., (1990) Ann. N.Y. Acad. Sci, 611, pp. 35-47; Nordmann, A., Blommers, M.J.J., Fretz, H., Arvinte, T., Drake, A.F., (1999) Eur. J. Biochem, 261 (1), pp. 216-226; Minth, C.D., Bloom, S.R., Polak, J.M., Dixon, J.E., (1984) Proc. Natl. Acad. Sci. U.S.A, 81 (14), pp. 4577-4581; Chronwall, B.M., DiMaggio, D.A., Massari, V.J., Pickel, V.M., Ruggiero, D.A., O'Donohue, T.L., (1985) Neuroscience, 15 (4), pp. 1159-1181; Wai, S.M., Kindler, P.M., Lam, E.T., Zhang, A., Yew, D.T., (2004) Cell Mol. Neurobiol, 24 (5), pp. 667-684; Sundler, F., Böttcher, G., Ekblad, E., Hakanson, R., (1993) The Biology of Neuropeptide Y and Related Peptides, pp. 157-196. , Colmers, W.F. and Wahlestedt, C, Ed, Humana Press, New Jersey, pp; Ekblad, E., Hakanson, R., Sundler, F., (1984) Regul. Pept, 10 (1), pp. 47-55; Cavadas, C., Silva, A.P., Mosimann, F., Cotrim, M.D., Ribeiro, C.A.F., Brunner, H.R., Grouzmann, E., (2001) J. Clin. Endocrinol. Metab, 86 (12), pp. 5956-5963; Silva, A.P., Cavadas, C., Grouzmann, E., (2002) Clin. Chim. Acta, 326 (1-2), pp. 3-25; Strand, F.L., (1999) Neuropeptides: Regulators of Physiological Processes, , MIT Press: Cambridge; Ericsson, A., Schalling, M., McIntrye, K.R., Lundberg, J.M., Larhammar, D., Seroogy, K., Hokfelt, T., Persson, H., (1987) Proc. Natl. Acad. Sci. U.S.A, 84 (16), pp. 5585-5589; Yang, K., Guan, H., Arany, E., Hill, D.J., Cao, X., (2008) FASEB J, 22 (7), pp. 2452-2464; Pedrazzini, T., Pralong, F., Grouzmann, E., (2003) Cell Mol. Life Sci, 60 (2), pp. 350-377; Blomqvist, A.G., Herzog, H., (1997) Trends Neurosci, 20 (7), pp. 294-298; Berglund, M.M., Schober, D.A., Statnick, M.A., McDonald, P.H., Gehlert, D.R., (2003) J. Pharmacol. Exp. Ther, 306 (1), pp. 147-156; Berglund, M., Hipskind, P., Gehlert, D., (2005) NPY Family of Peptides in Immune Disorders, Inflammation, Angiogenesis and Cancer, pp. 29-62. , Zukowska, Z. and Feuerstein, G.Z, Ed, Birkhaeuser Verlag, Switzerland, pp; Larhammar, D., Salaneck, E., (2004) Neuropeptides, 38 (4), pp. 141-151; Gregor, P., Feng, Y., DeCarr, L.B., Cornfield, L.J., McCaleb, M.L., (1996) J. Biol. Chem, 271 (44), pp. 27776-27781; Starbäck, P., Wraith, A., Eriksson, H., Larhammar, D., (2000) Biochem. Biophys. Res. Commun, 277 (1), pp. 264-269; Wraith, A., Törnsten, A., Chardon, P., Harbitz, I., Chowdhary, B.P., Andersson, L., Lundin, L.G., Larhammar, D., (2000) Genome Res, 10 (3), pp. 302-310; Larhammar, D., Wraith, A., Berglund, M.M., Holmberg, S.K.S., Lundell, I., (2001) Peptides, 22 (3), pp. 295-307; Larhammar, D., Blomqvist, A., Yee, F., Jazin, E., Yoo, H., Wahlested, C., (1992) Proc. Natl. Acad. Sci. U.S.A, 267 (16), pp. 10935-10938; Herzog, H., Hort, Y.J., Ball, H.J., Hayes, G., Shine, J., Selbie, L.A., (1992) Proc. Natl. Acad. Sci. U.S.A, 89 (13), pp. 5794-5798; Mullins, D.E., Zhang, X., Hawes, B.E., (2002) Regul. Pept, 105 (1), pp. 65-73; Krause, J., Eva, C., Seeburg, P.H., Sprengel, R., (1992) Mol. Pharmacol, 41 (5), pp. 817-821; Eva, C., Keinanen, K., Monyer, H., Seeburg, P., Sprengel, R., (1990) FEBS J, 271 (1-2), pp. 81-84; Nakamura, M., Sakanaka, C., Aoki, Y., Ogasawara, H., Tsuji, T., Kodama, H., Matsumoto, T., Noma, M., (1995) J. Biol. Chem, 270 (50), pp. 30102-30110; Álvaro, A.R., Martins, J., Araújo, I.M., Rosmaninho-Salgado, J., Ambrósio, A.F., Cavadas, C., (2008) J. Neurochem, , Epub ahead of print; Herzog, H., Baumgartner, M., Vivero, C., Selbie, L.A., Auer, B., Shine, J., (1993) J. Biol. Chem, 268 (9), pp. 6703-6707; Marklund, U., Byström, M., Gedda, K., Larefalk, A., Juneblad, K., Nyström, S., Ekstrand, A.J., (2002) Mol. Cell Endocrinol, 188 (1-2), pp. 85-97; Ball, H.J., Shine, J., Herzog, H., (1995) J. Biol. Chem, 270 (45), pp. 27272-27276; Ferguson, S.S., (2001) Pharmacol. Rev, 53 (1), pp. 1-24; Okamoto, T., Schlegel, A., Scherer, P.E., Lisanti, M.P., (1998) J. Biol. Chem, 273 (10), pp. 5419-5422; Fabry, M., Langer, M., Rothen-Rutishauser, B., Wunderli-Allenspach, H., Höcker, H., Beck-Sickinger, A.G., (2000) Eur. J. Biochem, 267 (17), pp. 5631-5637; Parker, S.L., Kane, J.K., Parker, M.S., Berglund, M.M., Lundell, I.A., Li, M.D., (2001) Eur. J. Biochem, 268 (4), pp. 877-886; Gicquiaux, H., Lecat, S., Gaire, M., Dieterlen, A., Mély, Y., Takeda, K., Bucher, B., Galzi, J.L., (2002) J. Biol. Chem, 277 (8), pp. 6645-6655; Ouedraogo, M., Lecat, S., Rochdi, M.D., Hachet-Haas, M., Matthes, H., Gicquiaux, H., Verrier, S., Bucher, B., (2008) Traffic, 9 (3), pp. 305-324; Holliday, N.D., Lam, C.W., Tough, I.R., Cox, H.M., (2005) Mol. Pharmacol, 67 (3), pp. 655-664; Broberger, C., Visser, T.J., Kuhar, M.J., Hökfelt, T., (1999) Neuroendocrinology, 70 (5), pp. 295-305; Kopp, J., Xu, Z.Q., Zhang, X., Pedrazzini, T., Herzog, H., Kresse, A., Wong, H., Hökfelt, T., (2002) Neurosci, 111 (3), pp. 443-532; Larsen, P.J., Tang-Christensen, M., Stidsen, C.E., Madsen, K., Smith, M.S., Cameron, J.L., (1999) J. Clin. Endocrinol. Metab, 84 (10), pp. 3781-3791; Wharton, J., Gordon, L., Byrne, J., Herzog, H., Selbie, L.A., Moore, K., Sullivan, M.H., Polak, J.M., (1993) Proc. Natl. Acad. Sci. U.S.A, 90 (2), pp. 687-691; Feth, F., Rascher, W., Michel, M.C., (1992) Br. J. Pharmacol, 105 (1), pp. 71-76; DiMaggio, D.A., Farah Jr, J.M., Westfall, T.C., (1994) Endocrinology, 134 (2), pp. 719-727; Dumont, Y., Quirion, R., (2006) Progress in Inflammation Research, pp. 7-33. , Feuernstein, G. and Zukowska-Grojec, Z, Ed, Birkhaeuser Verlag, Switzerland, pp; Balasubramaniam, A., (2003) Curr. Pharm. Des, 9 (15), pp. 1165-1175; Fuhlendorff, J., Gether, U., Aakerlund, L., Langeland-Johansen, N., Thogersen, H., Melberg, S.G., Olsen, U.B., Schwartz, T.W., (1990) Proc. Natl. Acad. Sci. U.S.A, 87 (1), pp. 182-186; Grandt, D., Feth, F., Rascher, W., Reeve Jr., J.R., Schlicker, E., Schimiczek, M., Layer, P., Michel, M.C., (1994) Eur. J. Pharmacol, 269 (2), pp. 127-132; Söll, R.M., Dinger, M.C., Lundell, I., Larhammer, D., Beck-Sickinger, A.G., (2001) Eur. J. Biochem, 268 (10), pp. 2828-2837; Mullins, D., Kirby, D., Hwa, J., Guzzi, M., Rivier, J., Parker, E., (2001) Mol. Pharmacol, 60 (3), pp. 534-540; Rudolf, K., Eberlein, W., Engel, W., Wieland, H.A., Willim, K.D., Entzeroth, M., Wienen, W., Doods, H.N., (1994) Eur. J. Pharmacol, 271 (2-3), pp. R11-R13; Wieland, H.A., Engel, W., Eberlein, W., Rudolf, K., Doods, H.N., (1998) Br. J. Pharmacol, 125 (3), pp. 549-555; Daniels, A.J., Matthews, J.E., Slepetis, R.J., Jansen, M., Viveros, O.H., Tadepalli, A., Harrington, W., Spaltenstein, A., (1995) Proc. Natl. Acad. Sci. U.S.A, 92 (20), pp. 9067-9071; Schober, D.A., Van Abbema, A.M., Smiley, D.L., Bruns, R.F., Gehlert, D.R., (1998) Peptides, 19 (3), pp. 537-542; Balasubramaniam, A., Dhawan, V.C., Mullins, D.E., Chance, W.T., Sheriff, S., Guzzi, M., Prabhakaran, M., Parker, E.M., (2001) J. Med. Chem, 44 (10), pp. 1479-1482; Daniels, A.J., Chance, W.T., Grizzle, M.K., Heyer, D., Matthews, J.E., (2001) Peptides, 22 (3), pp. 483-491; Hipskind, P.A., Lobb, K.L., Nixon, J.A., Britton, T.C., Bruns, R.F., Catlow, J., Dieckman-McGinty, D.K., Gehlert, D.R., (1997) J. Med. Chem, 40 (23), pp. 3712-3714; Schneider, E., Keller, M., Brennauer, A., Hoefelschweiger, B.K., Gross, D., Wolfbeis, O.S., Bernhardt, G., Buschauer, A., (2007) ChemBioChem, 8 (16), pp. 1981-1988; Serradeil-Le, G.C., Valeet, G., Rouby, P.E., Pellet, A., Oury-Donat, F., Brossard, G., Lespy, L., LeFur, G., (1995) FEBS Lett, 362 (2), pp. 192-196; Kanatani, A., Hata, M., Mashiko, S., Ishihara, A., Okamoto, O., Haga, Y., Ohe, T., Ihara, M., (2001) Mol. Pharmacol, 59 (3), pp. 501-505; Wahlestedt, C., Håkanson, R., (1986) Med. Biol, 64 (2-3), pp. 85-88; Doods, H.N., Wieland, H.A., Engel, W., Eberlein, W., Willim, K.D., Entzeroth, M., Wienen, W., Rudolf, K., (1996) Regul. Pept, 65 (1), pp. 71-77; Gerald, C., Walker, M.W., Criscione, L., Gustafson, E.L., Batzl-Hartmann, C., Smith, K.E., Vaysse, P., Weinshank, R.L., (1996) Nature, 382 (6587), pp. 168-171; Lin, S., Boey, D., Herzog, H., (2004) Neuropeptides, 38 (4), pp. 189-200; Pedrazzini, T., (2004) Neuropeptides, 38 (4), pp. 267-275; Pedrazzini, T., Seydoux, J., Künstner, P., Aubert, J.F., Grouzmann, E., Beermann, F., Brunner, H.R., (1998) Nat. Med, 4 (6), pp. 722-726; Kushi, A., Sasai, H., Koizumi, H., Takeda, N., Yokoyama, M., Nakamura, M., (1998) Proc. Natl. Acad. Sci. U.S.A, 95 (26), pp. 15659-15664; Naveilhan, P., Canals, J.M., Arenas, E., Ernfors, P., (2001) J. Neurochem, 78 (6), pp. 1201-1207; Thiele, T.E., Koh, M.T., Pedrazzini, T., (2002) J. Neurosci, 22 (3), pp. RC208-RC214; Karlsson, R.M., Choe, J.S., Cameron, H.A., Thorsell, A., Crawley, J.N., Holmes, A., Heilig, M., (2008) Psychopharmacology (Berlin, Ger.), 195 (4), pp. 547-557; Wheway, J., Mackay, C.R., Newton, R.A., Sainsbury, A., Boey, D., Herzog, H., Mackay, F., (2005) J. Exp. Med, 202 (11), pp. 1527-1538; Zukowska-Grojec, Z., Karwatowska-Prokopczuk, E., Fisher, T.A., Ji, H., (1998) Regul. Pept, 75-76, pp. 231-238; Hansel, D.E., Eipper, B.A., Ronnett, G.V., (2001) Nature, 410 (6831), pp. 940-944; Howell, O.W., Doyle, K., Goodman, J.H., Scharfman, H.E., Herzog, H., Pringle, A., Beck-Sickinger, A.G., Gray, W.P., (2005) J. Neurochem, 93 (3), pp. 560-570; Cho, Y.R., Kim, C.W., (2004) Biochem. Biophys. Res. Commun, 314 (3), pp. 773-780; Milenkovic, I., Weick, M., Wiedemann, P., Reichenbach, A., Bringmann, A., (2004) Graefe's Arch. Clin. Exp. Ophthalmol, 242 (11), pp. 944-950; Anitha, M., Chandrasekharan, B., Salgado, J.R., Grouzmann, E., Mwangi, S., Sitaraman, S.V., Srinivasan, S., (2006) Gastroenterology, 131 (4), pp. 1164-1178; Doyle, K.L., Karl, T., Hort, Y., Duffy, L., Shine, J., Herzog, H., (2008) J. Neurochem, 105 (3), pp. 641-652; Jacques, D., Abdel-Samad, D., (2007) Can. J. Physiol. Pharmacol, 85 (1), pp. 43-53; Agasse, F., Bernardino, L., Kristiansen, H., Christiansen, S.H., Ferreira, R., Silva, B., Grade, S., Malva, J.O., (2008) Stem Cells, 26 (6), pp. 1636-1645; Movafagh, S., Hobson, J.P., Spiegel, S., Kleinman, H.K., Zukowska, Z., (2006) FASEB J, 20 (11), pp. 1924-1926; Ruscica, M., Dozio, E., Boghossian, S., Bovo, G., Riaño, V.M., Motta, M., Magni, P., (2006) Endocrinology, 147 (3), pp. 1466-1473; Seger, R., Krebs, E.G., (1995) FASEB J, 9 (9), pp. 726-735; Kholodenko, B.N., (2002) Trends Cell Biol, 12 (4), pp. 173-177; Eva, C., Serra, M., Mele, P., Panzica, G.C., Oberto, A., (2006) Front. Neuroendocrinol, 27 (3), pp. 308-339; Elefteriou, F., Bone Cell Mol (2005) Life Sci, 62 (19-20), pp. 2339-2349; Chenu, C., (2004) J. Musculoskcl. Neuron. Interact, 4 (2), pp. 132-134; Allison, S.J., Baldock, P.A., Herzog, H., (2007) Peptides, 28 (2), pp. 320-325; Bjurholm, A., Kreicbergs, A., Terenius, L., Goldstein, M., Schultzberg, M., (1988) J. Auton. Nerv. Syst, 25 (2-3), pp. 119-125; Hill, E.L., Elde, R., (1991) Cell Tissue Res, 264 (3), pp. 469-480; Ahmad, T., Ugarph-Morawski, A., Li, J., Bileviciute-Ljungar, I., Finn, A., Ostenson, C.G., Kreicbergs, A., (2004) Regul. Pept, 119 (1-2), pp. 61-67; Togari, A., Arai, M., Mizutani, S., Mizutani, S., Koshihara, Y., Nagatsu, T., (1997) Neurosci. Lett, 233 (2-3), pp. 125-128; Lundberg, P., Allison, S.J., Lee, N.J., Baldock, P.A., Brouard, N., Rost, S., Enriquez, R.F., Herzog, H., (2007) J. Biol. Chem, 282 (26), pp. 19082-19091; Baldock, P.A., Sainsbury, A., Allison, S., Lin, E.J., Couzens, M., Boey, D., Enriquez, R., Gardiner, E.M., (2005) J. Bone Miner. Res, 20 (10), pp. 1851-1857; Ducy, P., Schinke, T., Karsenty, G., (2000) Science, 289 (5484), pp. 1501-1504; Takeda, S., Karsenty, G., (2001) J. Bone Miner. Metab, 19 (3), pp. 195-198; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., (2000) Cell, 100 (2), pp. 197-207; Stephens, T.W., Basinski, M., Bristow, P.K., Bue-Valleskey, J.M., Burgett, S.G., Craft, L., Hale, J., Heiman, M., (1995) Nature, 377 (6549), pp. 530-532; Erickson, J.C., Hollopeter, G., Palmiter, R.D., (1996) Science, 274 (5293), pp. 1704-1707; Allison, S.J., Baldock, P., Sainsbury, A., Enriquez, R., Lee, N.J., Lin, E.J., Klugmann, M., Gardiner, E.M., (2006) J. Biol. Chem, 281 (33), pp. 23436-23444; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., (1992) J. Bone Miner. Res, 7 (9), pp. 1011-1019; Bjurholm, A., Kreicbergs, A., Schultzberg, M., Lerner, U.H., (1998) Acta Physiol. Scand, 134 (3), pp. 451-462; Amano, S., Arai, M., Goto, S., Togari, A., (2007) Biochim. Biophys. Acta, 1770 (6), pp. 966-973; Baldock, P.A., Allison, S.J., Lundberg, P., Lee, N.J., Slack, K., Lin, E.J., Enriquez, R.F., Herzog, H., (2007) J. Biol. Chem, 282 (26), pp. 19092-19102
Keywords: 1 [1 [3 [(3 piperidyl)]]propyl] 2 [[(4 chlorophenoxyl)methyl]indol 3 yl] 2 (4 piperidylpiperidyl)ethan 1 one; 2 [1 (3 chloro 5 isopropoxycarbonylaminophenyl)ethylamino] 6 [2 (5 ethyl 4 methyl 2 thiazolyl)ethyl] 4 morpholinopyridine; 2 [1 (3 chloro 5 isopropyloxycarbonylaminophenyl)ethylamino] 6 [2 (5 ethyl 4 methyl 1,3 thiazol 2 yl)ethyl] 4 morpholinopyridine; Amino Acid Sequence; animal; Animals; bone development; bone mass; bone remodeling; Bone remodelling; bone turnover; Brain; drug antagonism; drug effect; drug potentiation; drug targeting; genetics; gi 264879a; gr 231118; Homeostasis; human; Humans; ligand; Ligands; ly 357897; metabolism; molecular genetics; Molecular Sequence Data; n alpha [3,3 bis(1 naphthyl)propionyl]dextro arginine n [1 benzyl 2 methoxyethyl]amide; n [1 [4 [[[[4 [(dimethylamino)methyl]cyclohexyl]methyl]amino]iminomethyl]benzyl] 2 oxo 2 (1 pyrrolidinyl)ethyl] alpha [(2 naphthalenylsulfonyl)amino]benzenepropanamide; n2 diphenylacetyl n (4 ureidomethylbenzyl)argininamide; nalpha (diphenylacetyl) n (4 hydroxybenzyl) dextro argininamide; neuropeptide Y; neuropeptide Y receptor; neuropeptide Y receptor agonist; neuropeptide Y receptor antagonist; neuropeptide Y [25 dextro arginine]; neuropeptide Y [26 dextro histidine]; neuropeptide Y [31 leucine 34 proline]; neuropeptide Y [6 arginine 34 proline]; neuropeptide Y [7 phenylalanine 34 proline]; neuropeptide Y1 receptor; neuropeptide Y2 receptor; neuropeptide Y4 receptor; neuropeptide Y5 receptor; neuropeptide Y6 receptor; nonhuman; osteoblast; osteoclast; osteolysis; peptide YY; peptide YY [31 leucine 34 proline]; peptide YY [34 proline]; pharmacological blocking; physiology; protein binding; protein expression; protein family; protein isolation; receptor intrinsic activity; Receptors, Neuropeptide Y; review; signal transduction; unclassified drug; Y1 receptor

Osteogenic differentiation of mesenchymal stem cells using PAMAM dendrimers as gene delivery vectors - Santos, J.L.; Oramas, E.; Pêgo, A.P.; Granja, P.L.; Tomás, H. (Journal of Controlled ReleaseJ. Control. Release, 2009)
This paper reports the use of different generations of polyamidoamine (PAMAM) dendrimers for the in vitro transfection of mesenchymal stem cells (MSCs). A systematic study was carried out on the transfection efficiency achieved by the PAMAM dendrimers using a β-galactosidase reporter gene system. Transfection results were shown to be dependent upon the generation of dendrimers, the amine to phosphate group ratio and the cell passage number. In all cases, the transfection efficiency was very low. Nevertheless, it was hypothesized that a low transfection level could be sufficient to promote the in vitro differentiation of MSCs towards the osteoblastic lineage. To address this possibility, dendrimers carrying the human bone morphogenetic protein-2 (hBMP-2) gene-containing plasmid were used. All quantitative (alkaline phosphatase activity, osteocalcin secretion and calcium deposition) and qualitative (von Kossa staining) osteogenic markers were significantly stronger in transfected cells when compared to non-transfected ones. This study not only clearly demonstrates that a low transfection level can be sufficient for inducing in vitro differentiation of MSCs to the osteoblast phenotype but also highlights the importance of focusing research on the development of gene delivery vectors in the concrete application. © 2008 Elsevier B.V. All rights reserved.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: JCREEdoi: 10.1016/j.jconrel.2008.11.007PubMed ID: 19070635Language of Original Document: EnglishCorrespondence Address: Tomás, H.; Centro de Química da Madeira, Departamento de Química, Universidade da Madeira, Campus Universitario da Penteada, 9000-390 Funchal, Portugal; email: lenat@uma.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium, 14092-94-5, 7440-70-2; osteocalcin, 136461-80-8; phosphate, 14066-19-4, 14265-44-2; BMP2 protein, human; Bone Morphogenetic Protein 2; Dendrimers; PAMAM Starburst; Polyamines; beta-Galactosidase, 3.2.1.23References: Dai, J., Rabie, A.B.M., Hagg, U., Xu, R.A., Alternative gene therapy strategies for the repair of craniofacial bone defects (2004) Curr. Gene Ther., 4 (4), pp. 469-485;Gersbach, C.A., Phillips, J.E., Garcia, A.J., Genetic engineering for skeletal regenerative medicine (2007) Annu. Rev. Biomed. Eng., 9, pp. 87-119; Kofron, M.D., Laurencin, C.T., Orthopaedic applications of gene therapy (2005) Curr. Gene Ther., 5 (1), pp. 37-61; Kofron, M.D., Laurencin, C.T., Bone tissue engineering by gene delivery (2006) Adv. Drug Deliv. Rev., 58 (4), pp. 555-576; Luo, J., Sun, M.H., Kang, Q., Peng, Y., Jiang, W., Luu, H.H., Luo, Q., He, T.C., Gene therapy for bone regeneration (2005) Curr. Gene Ther., 5 (2), pp. 167-179; Partridge, K.A., Oreffo, R.O., Gene delivery in bone tissue engineering: progress and prospects using viral and nonviral strategies (2004) Tissue Eng., 10 (1-2), pp. 295-307; Turgeman, G., Aslan, H., Gazit, Z., Gazit, D., Cell-mediated gene therapy for bone formation and regeneration (2002) Curr. Opin. Mol. Ther., 4 (4), pp. 390-394; Chen, Y., Cheung, K.M.C., Kung, H.F., Leong, J.C.Y., Lu, W.W., Luk, K.D.K., In vivo new bone formation by direct transfer of adenoviral-mediated bone morphogenetic protein-4 gene (2002) Biochem. Biophys. Res. Commun., 298 (1), pp. 121-127; Lieberman, J.R., Daluiski, A., Stevenson, S., Wu, L., McAllister, P., Lee, Y.P., Kabo, J.M., Witte, O.N., The effect of regional gene therapy with bone morphogenetic protein-2-producing bone-marrow cells on the repair of segmental femoral defects in rats (1999) J. Bone Joint Surg. Am., 81 (7), pp. 905-917; Park, J., Ries, J., Gelse, K., Kloss, F., von der Mark, K., Wiltfang, J., Neukam, F.W., Schneider, H., Bone regeneration in critical size defects by cell-mediated BMP-2 gene transfer: a comparison of adenoviral vectors and liposomes (2003) Gene Ther., 10 (13), pp. 1089-1098; Riew, K.D., Wright, N.M., Cheng, S.L., Avioli, L.V., Lou, J., Induction of bone formation using a recombinant adenoviral vector carrying the human BMP-2 gene in a rabbit spinal fusion model (1998) Calcif. Tissue Int., 63 (4), pp. 357-360; Tsuda, H., Wada, T., Ito, Y., Uchida, H., Dehari, H., Nakamura, K., Sasaki, K., Hamada, H., Efficient BMP2 gene transfer and bone formation of mesenchymal stem cells by a fiber-mutant adenoviral vector (2003) Mol. Ther., 7 (3), pp. 354-365; De Laporte, L., Cruz Rea, J., Shea, L.D., Design of modular non-viral gene therapy vectors (2006) Biomaterials, 27 (7), pp. 947-954; Eliyahu, H., Barenholz, Y., Domb, A.J., Polymers for DNA delivery (2005) Molecules, 10 (1), pp. 34-64; Roth, C.M., Sundaram, S., Engineering synthetic vectors for improved DNA delivery: insights from intracellular pathways (2004) Annu. Rev. Biomed. Eng., 6, pp. 397-426; Corsi, K., Chellat, F., Yahia, L., Fernandes, J.C., Mesenchymal stem cells, MG63 and HEK293 transfection using chitosan-DNA nanoparticles (2003) Biomaterials, 24 (7), pp. 1255-1264; Hamm, A., Krott, N., Breibach, I., Blindt, R., Bosserhoff, A.K., Efficient transfection method for primary cells (2002) Tissue Eng., 8 (2), pp. 235-245; Lakshmipathy, U., Pelacho, B., Sudo, K., Linehan, J.L., Coucouvanis, E., Kaufman, D.S., Verfaillie, C.M., Efficient transfection of embryonic and adult stem cells (2004) Stem Cells, 22 (4), pp. 531-543; Kim, S.W., Ogawa, T., Tabata, Y., Nishimura, I., Efficacy and cytotoxicity of cationic-agent-mediated nonviral gene transfer into osteoblasts (2004) J. Biomed. Mater. Res. A, 71 (2), pp. 308-315; Dufes, C., Uchegbu, I.F., Schatzlein, A.G., Dendrimers in gene delivery (2005) Adv. Drug Deliv. Rev., 57 (15), pp. 2177-2202; Guillot-Nieckowski, M., Eisler, S., Diederich, F., Dendritic vectors for gene transfection (2007) New J. Chem., 31 (7), pp. 1111-1127; Svenson, S., Tomalia, D.A., Dendrimers in biomedical applications-reflections on the field (2005) Adv. Drug Deliv. Rev., 57 (15), pp. 2106-2129; Haensler, J., Szoka, F.C., Polyamidoamine cascade polymers mediate efficient transfection of cells in culture (1993) Bioconjug. Chem., 4 (5), pp. 372-379; Choi, J.S., Nam, K., Park, J., Kim, J.B., Lee, J.K., Park, J., Enhanced transfection efficiency of PAMAM dendrimer by surface modification with l-arginine (2004) J. Control. Release, 99 (3), pp. 445-456; Kono, K., Akiyama, H., Takahashi, T., Takagishi, T., Harada, A., Transfection activity of polyamidoamine dendrimers having hydrophobic amino acid residues in the periphery (2005) Bioconjug. Chem., 16 (1), pp. 208-214; KukowskaLatallo, J.F., Bielinska, A.U., Johnson, J., Spindler, R., Tomalia, D.A., Baker, J.R., Efficient transfer of genetic material into mammalian cells using Starburst polyamidoamine dendrimers (1996) Proc. Natl. Acad. Sci. U. S. A., 93 (10), pp. 4897-4902; Gebhart, C.L., Kabanov, A.V., Evaluation of polyplexes as gene transfer agents (2001) J. Control. Release, 73 (2), pp. 401-416; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J. Cell. Biochem., 72 (3), pp. 396-410; Lennon, D.P., Haynesworth, S.E., Young, R.G., Dennis, J.E., Caplan, A.I., A chemically-defined medium supports in-vitro proliferation and maintains the osteochondral potential of rat marrow-derived mesenchymal stem-cells (1995) Exp. Cell Res., 219 (1), pp. 211-222; Bielinska, A.U., Chen, C.L., Johnson, J., Baker, J.R., DNA complexing with polyamidoamine dendrimers: implications for transfection (1999) Bioconjug. Chem., 10 (5), pp. 843-850; Eichman, J.D., Bielinska, A.U., Kukowska-Latallo, J.F., Baker Jr., J.R., The use of PAMAM dendrimers in the efficient transfer of genetic material into cells (2000) Pharm. Sci. Technol. Today, 7, pp. 232-245; Haleem-Smith, H., Derfoul, A., Okafor, C., Tuli, R., Olsen, D., Hall, D.J., Tuan, R.S., Optimization of high-efficiency transfection of adult human mesenchymal stem cells in vitro (2005) Mol. Biotechnol., 30 (1), pp. 9-19; Fischer, D., Li, Y.X., Ahlemeyer, B., Krieglstein, J., Kissel, T., In vitro cytotoxicity testing of polycations: influence of polymer structure on cell viability and hemolysis (2003) Biomaterials, 24 (7), pp. 1121-1131; Jevprasesphant, R., Penny, J., Jalal, R., Attwood, D., McKeown, N.B., D'Emanuele, A., The influence of surface modification on the cytotoxicity of PAMAM dendrimers (2003) Int. J. Pharm., 252 (1-2), pp. 263-266; Wilke, M., Fortunati, E., vandenBroek, M., Hoogeveen, A.T., Scholte, B.J., Efficacy of a peptide-based gene delivery system depends on mitotic activity (1996) Gene Ther., 3 (12), pp. 1133-1142; Xie, Y.B., Yang, S.T., Kniss, D.A., Three-dimensional cell-scaffold constructs promote efficient gene transfection: implications for cell-based gene therapy (2001) Tissue Eng., 7 (5), pp. 585-598; Yamagiwa, H., Endo, N., Tokunaga, K., Hayami, T., Hatano, H., Takahashi, H.E., In vivo bone-forming capacity of human bone marrow-derived stromal cells is stimulated by recombinant human bone morphogenetic protein-2 (2001) J. Bone Miner. Metab., 19 (1), pp. 20-28; Chaudhari, A., Ron, E., Rethman, M.P., Recombinant human bone morphogenetic protein-2 stimulates differentiation in primary cultures of fetal rat calvarial osteoblasts (1997) Mol. Cell. Biochem., 167 (1-2), pp. 31-39; Hay, E., Hott, M., Graulet, A.M., Lomri, A., Marie, P.J., Effects of bone morphogenetic protein-2 on human neonatal calvaria cell differentiation (1999) J. Cell. Biochem., 72 (1), pp. 81-93; Yamaguchi, A., Regulation of differentiation pathway of skeletal mesenchymal cells in cell-lines by transforming growth-factor-beta superfamily (1995) Semin. Cell Biol., 6 (3), pp. 165-173; Yamaguchi, A., Ishizuya, T., Kintou, N., Wada, Y., Katagiri, T., Wozney, J.M., Rosen, V., Yoshiki, S., Effects of BMP-2, BMP-4, and BMP-6 on osteoblastic differentiation of bone marrow-derived stromal cell lines, ST2 and MC3T3-G2/PA6 (1996) Biochem. Biophys. Res. Commun., 220 (2), pp. 366-371; Baltzer, A.W.A., Lattermann, C., Whalen, J.D., Wooley, P., Weiss, K., Grimm, M., Ghivizzani, S.C., Evans, C.H., Genetic enhancement of fracture repair: healing of an experimental segmental defect by adenoviral transfer of the BMP-2 gene (2000) Gene Ther., 7 (9), pp. 734-739; Wang, E.A., Rosen, V., Dalessandro, J.S., Bauduy, M., Cordes, P., Harada, T., Israel, D.I., Wozney, J.M., Recombinant human bone morphogenetic protein induces bone-formation (1990) Proc. Natl. Acad. Sci. U. S. A., 87 (6), pp. 2220-2224; Chuang, C.K., Sung, L.Y., Hwang, S.M., Lo, W.H., Chen, H.C., Hu, Y.C., Baculovirus as a new gene delivery vector for stem cell engineering and bone tissue engineering (2007) Gene Ther., 14 (19), pp. 1417-1424; Aslan, H., Zilberman, Y., Arbeli, V., Sheyn, D., Matan, Y., Liebergall, M., Li, J.Z., Gazit, Z., Nucleofection-based ex vivo nonviral gene delivery to human stem cells as a platform for tissue regeneration (2006) Tissue Eng., 12 (4), pp. 877-889; Noel, D., Gazit, D., Bouquet, C., Apparailly, F., Bony, C., Plence, P., Millet, V., Jorgensen, C., Short-term BMP-2 expression is sufficient for in vivo osteochondral differentiation of mesenchymal stem cells (2003) Stem Cells, 22 (1), pp. 74-85
Keywords: alkaline phosphatase; amine; Amines; animal cell; Animals; article; beta galactosidase; beta-Galactosidase; Bone; Bone morphogenetic protein; bone morphogenetic protein 2; Bone Regeneration; Calcium; Cell culture; cell differentiation; Cell Line; cell lineage; cell survival; Cells; Cells, Cultured; controlled study; dendrimer; Dendrimers; embryo; enzyme activity; Flowcharting; gene expression; Gene transfer; Gene Transfer Techniques; gene vector; Genes, Reporter; genetic transfection; human; human cell; Humans; in vitro study; Kidney; male; Mesenchymal stem cell; Mesenchymal Stem Cells; nonhuman; Nonviral gene delivery; nonviral gene delivery system; Nucleic acids; osteoblast; osteocalcin; Osteogenesis; PAMAM dendrimers; phosphate; plasmid; Plasmids; polyamidoamine; Polyamines; priority journal; protein secretion; Proteins; qualitative analysis; quantitative analysis; rat; Rats; Rats, Wistar; reporter gene; staining

Physical characterization of hydroxyapatite porous scaffolds for tissue engineering - Teixeira, S.; Rodriguez, M.A.; Pena, P.; De Aza, A.H.; De Aza, S.; Ferraz, M.P.; Monteiro, F.J. (Materials Science and Engineering CMater. Sci. Eng. C, 2009)
The present study refers to the preparation and characterization of porous hydroxyapatite scaffolds to be used as matrices for bone regeneration or as specific release vehicles. Ceramics are widely used for bone tissue engineering purposes and in this study, hydroxyapatite porous scaffolds were produced using the polymer replication method. Polyurethane sponges were used as templates and impregnated with a ceramic slurry at different ratios, and sintered at 1300 °C following a specific thermal cycle. The characteristics of the hydroxyapatite porous scaffolds and respective powder used as starting material, were investigated by using scanning electron microscopy, particle size distribution, X-ray diffraction, Fourier transformed infrared spectroscopy and compressive mechanical testing techniques. It was possible to produce highly porous hydroxyapatite scaffolds presenting micro and macropores and pore interconnectivity. © 2008 Elsevier B.V. All rights reserved.
Cited By (since 1996): 16Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.msec.2008.09.052Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: smsilva@ineb.up.ptReferences: Jones, A.C., Milthorpe, B., Averdunk, H., Limaye, A., Senden, T.J., Sakellariou, A., (2004) Biomaterials, 25 (20), p. 4947;Karageorgiou, V., Kaplan, D., (2005) Biomaterials, 26 (27), p. 5474; Sepulveda, P., Ortega, F.S., Innocentini, M.D.M., Pandolfelli, V.C., (2000) Journal of the American Ceramic Society, 83 (12), p. 3021; Woodard, J.R., Hilldore, A.J., Lan, S.K., Park, C.J., Morgan, A.W., Eurell, J.A., (2007) Biomaterials, 28 (1), p. 45; Harris, L.D., Kim, B.S., Mooney, D.J., (1998) Journal of Biomedical Materials Research, 42 (3), p. 396; Cyster, L.A., Grant, D.M., Howdle, S.M., Rose, F.R., Irvine, D.J., Freeman, D., (2005) Biomaterials, 26 (7), p. 697; Fu, Q., Rahaman, M.N., Bal, B.S., Huang, W., Day, D.E., (2007) Journal of Biomedical Materials Research A, 82 (1), p. 222; Chang, B.S., Lee, C.K., Hong, K.S., Youn, H.J., Ryu, H.S., Chung, S.S., (2000) Biomaterials, 21 (12), p. 1291; Chu, T.M., Orton, D.G., Hollister, S.J., Feinberg, S.E., Halloran, J.W., (2002) Biomaterials, 23 (5), p. 1283; Fu, Q., Rahaman, M.N., Dogan, F., Bal, B.S., (2007) Journal of Biomedical Materials Research B, Applied Biomaterials; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., (2004) Advanced Materials Forum Ii, 455-456, p. 358; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., (2004) Bioceramics, 254-2, p. 997. , (16); Teixeira, S., Ferraz, M.P., Monteiro, F.J., (2008) Journal of Materials Science-Materials in Medicine, 19 (2), p. 855; de Groot, K., (1980) Biomaterials, 1 (1), p. 47; Heise, U., Osborn, J.F., Duwe, F., (1990) International Orthopaedics, 14 (3), p. 329; Kuboki, Y., Takita, H., Kobayashi, D., Tsuruga, E., Inoue, M., Murata, M., (1998) Journal of Biomedical Materials Research, 39 (2), p. 190; Ramay, H.R., Zhang, M., (2003) Biomaterials, 24 (19), p. 3293; Kim, H.W., Knowles, J.C., Kim, H.E., (2005) Journal of Materials Science, 16 (3), p. 189; Iwano, T., Kurosawa, H., Murase, K., Takeuchi, H., Ohkubo, Y., (1991) Clinical Orthopaedics and Related Research, 268, p. 243; Tieliewuhan, Y., Hirata, I., Sasaki, A., Minagi, H., Okazaki, M., (2004) Dental Materials Journal, 23 (3), p. 258; Yunoki, S., Ikoma, T., Tsuchiya, A., Monkawa, A., Ohta, K., Sotome, S., (2007) Journal of Biomedical Materials Research B, Applied Biomaterials, 80 (1), p. 166; Zhang, Q.Q., Ren, L., Wang, C., Liu, L.R., Wen, X.J., Liu, Y.H., (1996) Artificial Cells, Blood Substitutes, and Immobilization Biotechnology, 24 (6), p. 693; Zhang, S.M., Cui, F.Z., Liao, S.S., Zhu, Y., Han, L., (2003) Journal of Materials Science, 14 (7), p. 641; Yunoki, S., Ikoma, T., Monkawa, A., Marukawa, E., Sotome, S., Shinomiya, K., (2007) Journal of Biomaterials Science, 18 (4), p. 393; Teixeira, S., Oliveira, S., Ferraz, M.P., Monteiro, F.J., (2008) Key Engineering Materials, 361-363 (II), p. 947; Gibson, I.R., Best, S.M., Bonfield, W., (1999) Journal of Biomedical Materials Research, 44 (4), p. 422; Kamitakahara, M., Ohtsuki, C., Kozaka, Y., Ogata, S., Tanihara, M., Miyazaki, T., (2006) Journal of the Ceramic Society of Japan, 114 (1325), p. 82; Kim, H.W., Deng, Y., Miranda, P., Pajares, A., Kim, D.K., Kim, H.E., (2001) Effect of Flaw State on the Strength of Brittle Coatings on Soft Substrates, p. 2377
Keywords: Apatite; Bone; Bone regenerations; Bone tissue engineerings; Ceramic materials; Ceramic slurries; Fourier-transformed infrared spectroscopies; hydroxyapatite; infrared spectroscopy; Macro-pores; Mechanical testing; Physical characterizations; Polymer blends; Polymer replications; Polymers; Polyurethane sponges; Pore interconnectivity; Porous hydroxyapatites; Porous scaffolds; Scaffolds; Scanning electron microscopy; Spectroscopic analysis; Starting materials; Thermal cycles; Tissue engineering; X- ray diffractions

Physical, chemical and in vitro biological profile of chitosan hybrid membrane as a function of organosiloxane concentration - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Costa, M.A.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
We attempted to prepare chitosan-silicate hybrid for use in a medical application and evaluated the physico-chemical properties and osteocompatibility of the hybrids as a function of γ-glycidoxypropyltrimethoxysilane (GPTMS) concentration. Chitosan-silicate hybrids were synthesized using GPTMS as the reagent for cross-linking of the chitosan chains. Fourier transform infrared spectroscopy, 29Si CP-MAS NMR spectroscopy and the ninhydrin assay were used to analyze the structures of the hybrids, and stress-strain curves were recorded to estimate their Young's modulus. The swelling ability, contact angle and cytocompatibility of the hybrids were investigated as a function of the GPTMS concentration. A certain fraction of GPTMS in each hybrid was linked at the epoxy group to the amino group of chitosan, which was associated with the change in the methoxysilane group of GPTMS due to hybridization. The cross-linking density was around 80% regardless of the volume of GPTMS. As the content of GPTMS increased, the water uptake decreased and the hydrophilicity of the hybrids increased except when the content exceeded amolar ratio of 1.5, when it caused a decrease. The values of the mechanical parameters assessed indicated that significant stiffening of the hybrids was obtained by the addition of GPTMS. The adhesion and proliferation of the MG63 osteoblast cells cultured on the chitosan-GPTMS hybrid surface were improved compared to those on the chitosan membrane, regardless of the GPTMS concentration. Moreover, human bone marrow osteoblast cells proliferated on the chitosan-GPTMS hybrid surface and formed a fibrillar extracellular matrix with numerous calcium phosphate globular structures, both in the presence and in the absence of dexamethasone. Therefore, the chitosan-GPTMS hybrids are promising candidates for basic materials that can promote bone regeneration because of their controllable composition (chitosan/GPTMS ratio). © 2008 Acta Materialia Inc.
Cited By (since 1996): 10Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.07.022PubMed ID: 18722166Language of Original Document: EnglishCorrespondence Address: Hayakawa, S.; Biomaterial Laboratory, Graduate School of Natural Science and Technology, Okayama University, Tsushima, Okayama-shi, 700-8530, Japan; email: satoshi@cc.okayama-u.ac.jpChemicals/CAS: (3 glycidyloxypropyl)trimethoxysilane, 2530-83-8; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; chitosan, 9012-76-4; silicate, 12627-13-3; Chitosan, 9012-76-4; Cross-Linking Reagents; gamma-glycidoxypropyltrimethoxysilane, 2530-83-8; Silanes; SiloxanesTradenames: AldrichReferences: Lai, J.Y., Lin, F.C., Wang, C.C., Wang, D.M., Effect of nonsolvent additives on the porosity and morphology of asymmetric TPX membranes [J] (1996) J Membrane Sci, 118, pp. 49-61;Wang, D.M., Lin, F.C., Chiang, J.C., Lai, J.Y., Control of porosity of asymmetric TPX membranes [J] (1998) J Membrane Sci, 141, pp. 1-12; Piattelli, A., Scarano, A., Russo, P., Matarasso, S., Evaluation of guided bone regeneration in rabbit tibia using bioresorbable and non-resorbable membranes (1996) Biomaterials, 17 (8), pp. 791-796; Gotfredsen, K., Nimb, L., Hjorting-Hansen, E., Immediate implant placement using a biodegradable barrier, polyhydroxybutyratehydroxyvalerate reinforced with polyglactin 910: an experimental study in dogs (1994) Clin Oral Implants Res, 5 (2), pp. 83-91; Kostopoulos, L., Karring, T., Augmentation of the rat mandible using guided tissue regeneration (1994) Clin Oral Implants Res, 5 (2), pp. 75-82; Kostopoulos, L., Karring, T., Guided bone regeneration in mandibular defects in rats using a bioresorbable polymer (1994) Clin Oral Implants Res, 5 (2), pp. 666-674; Nyman, S., Gottlow, J., Karring, T., The regeneration potential of the periodontal ligament: an experimental study in the monkey (1982) J Clin Periodontal, 9, pp. 257-265; Dupoirieux, L., Pourquier, D., Picot, M.C., Neves, M., Comparative study of three different membranes for guided bone regeneration of rat cranial defects (2001) Int J Oral Maxillofac Surg, 30 (1), pp. 58-62; Zhang, R., Ma, P.X., Porous poly(l-lactic acid)/apatite composites created by biomimetic process (1999) J Biomed Mater Res, 45, pp. 285-293; Murphy, W.L., Kohn, D.H., Mooney, D.J., Growth of continuous bonelike mineral within porous poly(lactide-co-glycolide) scaffolds in vitro (2000) J Biomed Mater Res, 50, pp. 50-58; Lin, F.C., Wang, D.M., Lai, J.Y., Asymmetric TPX membranes. J membranes with high gas flux. (1996) J Membrane Sci, 110, pp. 25-36; Vert, M., Mauduit, J., Li, S., Biodegradation of PLA/GA polymers: increasing complexity (1994) Biomaterials, 15, pp. 1209-1213; Lee, Y.K., Mooney, D.J., Hydrogels for tissue enigineering (2001) Chem Rev, 101, pp. 1869-1879; Domard, A., Rinaudo, M., Preparation and characterization fully deacetylated chitosan (1983) Int J Biol Macromol, 5, pp. 49-52; Chandy, T., Sharma, P.C., Chitosan - as a biomaterial (1990) Biomater Artif Cells Artif Organo, 18, pp. 1-24; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Accelerating effects of chitosan for healing at early phase of experimental open wound in dogs (1999) Biomaterials, 20, pp. 1407-1414; Muzzareli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Stimulatory effect on bone formation exerted by a modified chitosan (1994) Biomaterials, 15, pp. 1075-1081; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes (2005) Biomaterials, 26, pp. 485-493; Prochazkova, S., Varum, K.M., Æstgaard. Quantitative determination of chitosans by ninhydrin (1999) Carbohydr Polym, 38, pp. 115-122; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Coelho, M.J., Cabral, A.T., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in D-MEM (2000) Biomaterials, 21, pp. 1087-1094; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethhylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Argüelles-Monal, W., Desbriéres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J Non Cryst Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Incorporation of Ca 2+ ions in gelatin-siloxane hybrids through a sol-gel process (2001) J Ceram Soc Jpn, 109, pp. 403-408; Rashidova, S.S.h., Shakarova, D.S.h., Ruzimuradov, O.N., Satabaldieva, D.T., Zalyalieva, S.V., Shpigun, O.A., Bionanocompositional chitosan-silica sorbent for liquid chromatography (2004) J Chromatogr B, 800, pp. 49-53; Hench, L.L., Ethridge, E.C., (1982) Biomaterials an interfacial approach, , Academic Press, New York 10; Xynos, I.D., Hukkanen, M.V.J., Batten, J.J., Buttery, L.D., Hench, L.L., Polak, J.M., Bioglass ® 45S5 stimulates osteoblast turnover and enhances bone formation in vitro: implications and applications for bone tissue engineering (2000) Calcif Tissue Int, 67, pp. 321-329; Xynos, I.D., Edgar, A.J., Buttery, L.D.K., Hench, L.L., Ionic products of bioactive glass dissolution increase proliferation of human osteoblasts and induce insulin-like growth factor II mRNA expression and protein synthesis (2000) Biochem Biophys Res Commun, 276, pp. 461-465; Gough, J.E., Jones, J.R., Hench, L.L., Nodule formation and mineralisation of human primary osteoblasts cultured on a porous bioactive glass scaffold (2004) Biomaterials, 25, pp. 2039-2046; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci Mater Med, 8, pp. 61-65; Costa, M.A., Gutierres, M., Almeida, L., Lopes, M.A., Santos, J.D., Fernandes, M.H., In vitro mineralization of human bone marrow cells cultured on Bonelike ® (2004) Key Eng Mater, 254-256, pp. 821-824
Keywords: (3 glycidyloxypropyl)trimethoxysilane; article; assay; Biocompatibility; Bone Marrow Cells; calcium phosphate; cell adhesion; Cell Line, Tumor; cell proliferation; cell survival; cell viability; Chemical analysis; chitosan; concentration (parameters); controlled study; cross linking; Cross-Linking Reagents; extracellular matrix; human; human cell; Humans; hydrophobicity; in vitro study; infrared spectroscopy; Magnetic Resonance Spectroscopy; Microscopy, Electron, Scanning; molecular hybridization; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteocompatibility; physical chemistry; priority journal; Silanes; silicate; siloxane; Siloxanes; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; stress strain relationship; structure analysis; surface property; Tissue engineering; unclassified drug; water transport; γ-Glycidoxypropyltrimethoxysilane (GPTMS)

Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals - Costa, A.; Ayres-de-Campos, D.; Costa, F.; Santos, C.; Bernardes, J. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2009)
Objective: The objective of the study was to evaluate the accuracy of computer analysis of fetal heart rate (FHR) and ST event signals in prediction of neonatal acidemia. Study Design: One hundred forty-eight FHR tracings were evaluated to identify red alerts provided by the system, based on automated analysis of FHR and ST event signals, and compared with the occurrence of umbilical artery acidemia (pH ≤7.05). Results: The presence of red alerts obtained sensitivity of 1.00 (95% confidence interval [CI], 0.56-1.00), specificity of 0.94 (95% CI, 0.89-0.97), positive predictive value (PPV) of 0.47 (95% CI, 0.22-0.72), negative predictive value (NPV) of 1 (95% CI, 0.96-1.00), positive likelihood ratio (PLR) of 17.6 (95% CI, 9.0-34.5), and negative likelihood ratio (NLR) of 0. When limiting analysis to red alerts that did not include ST data, sensitivity was 0.57 (95% CI, 0.20-0.88), specificity was 0.97 (95% CI, 0.92-0.99), PPV was 0.50 (95% CI, 0.17-0.82), NPV was 0.98 (95% CI, 0.93-0.99), PLR was 20.14 (95% CI, 6.3-64.2), and NLR was 0.44 (95% CI, 0.19-1.04). Conclusion: Computer analysis of FHR and ST event signals provide higher accuracy in predicting neonatal academia. © 2009 Mosby, Inc. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: AJOGAdoi: 10.1016/j.ajog.2009.04.033PubMed ID: 19539895Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina, Hospital S. JoãoPortugal; email: cosantonia@gmail.comReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales, and Northern Ireland, , CEMACH (Confidential Enquiry into Maternal and Child Health), Confidential Enquiry into Maternal and Child Health, London, UK;(1997) 4th annual report, , CESDI (Confidential Enquiry into Stillbirths and Deaths in Infancy), Maternal and Child Health Research Consortium, London, UK; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Donker, D.K., van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-28; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labour (2006) Cochrane Database Syst Rev, 3; Doria, V., Papageorghiou, A., Gustafsson, A., Ugwumadu, A., Farrer, K., Arulkumaran, S., Review of the first 1502 cases of ECG-ST waveform analysis during labour in a teaching hospital (2007) BJOG, 114, pp. 1202-1207; Westerhuis, M., Kwee, A., van Ginkel, A., Drogtrop, A., Gyselaers, W., Visser, G., Limitations of ST analysis in clinical practice: three cases of intrapartum metabolic acidosis (2007) BJOG, 114, pp. 1194-1201; Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) BJOG, 114, pp. 1191-1193; Dawes, G.S., Redman, C.W., Smith, J.H., Improvements in the registration and analysis of fetal heart rate records at the bedside (1985) Br J Obstet Gynaecol, 92, pp. 317-325; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60. , SisPorto Multicentre Validation Study Group; Dawes, G.S., Moulden, M., Redman, C.W.G., System 8000: computerized antenatal FHR analysis (1991) J Perinat Med, 19, pp. 47-51; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J.P., Pereira-Leite, L., SisPorto 2.0-a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto® 3.5-a central fetal monitoring station with online alerts based on computerized cardiotocogram+S.T.event analysis (2008) J Perinat Med, 36, pp. 260-264; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) BJOG, 114, pp. 1446-1447; Downing, J.W., Houlton, P.C., Barclay, A., Extradural analgesia for cesarean section: a comparison with general anesthesia (1979) Br J Anaesth, 51, pp. 367-374; Crawford, J.S., James, F.M., Davies, P., Crawley, M., A further study of general anaesthesia for cesarean section (1976) Br J Anaesth, 48, pp. 661-667; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-175; ACOG technical bulletin. Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-310; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: a time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-1063; Low, J.A., Intrapartum fetal asphyxia: definition, diagnosis and classification (1997) Am J Obstet Gynecol, 176, pp. 957-959; Fleiss, J.L., (1981) Statistical methods for rates and proportions. 2nd ed., , John Wiley & Sons, New York, NY Section 5.6; Keith, R.D., Beckley, S., Garibaldi, J.M., Westgate, J.A., Ifeachor, E.C., Greene, K.R., A multicentre comparative study of 17 experts and an intelligent computer system for managing labour using cardiotocogram (1995) Br J Obstet Gynecol, 102, pp. 668-700; Chung, T.K., Mohajer, M.P., Yang, Z.j., Chang, A.M., Sahota, D.S., The prediction of fetal acidosis at birth by computerised analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Policy statement. The Apgar score-American Academy of Pediatrics and American College of Obstetricians and Gynecologists (2006) Pediatrics, 117, pp. 1444-1447; Casey, B.M., McIntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of the newborn infants (2001) N Engl J Med, 334, pp. 467-471; Moster, D., Lie, R.T., Irgens, L.M., Bjerkedal, T., Markestad, The association of Apgar score with subsequent death and cerebral palsy: a population-based study in term infants (2001) J Pediatr, 138, pp. 798-803
Keywords: acidemia; Acidosis; article; autoanalysis; Cardiotocography; computer analysis; computer assisted; computer prediction; Diagnosis, Computer-Assisted; diagnostic value; Electrocardiography; Female; Fetal heart rate; Fetal hypoxia; Fetal monitoring; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; Infant, Newborn; major clinical study; male; newborn; newborn acidosis; observational study; pH; Predictive Value of Tests; priority journal; Prospective Studies; prospective study; Reproducibility of Results; sensitivity and specificity; signal transduction; ST segment; umbilical artery

Protein adsorption and clotting time of pHEMA hydrogels modified with C18 ligands to adsorb albumin selectively and reversibly - Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2009)
This work intended to create a nanostructured biomaterial that would bind albumin in a selective and reversible way in order to inhibit the adsorption of other blood proteins and therefore minimize activation of coagulation. Different levels of C18 ligand have been immobilized on poly(2-hydroxyethyl methacrylate) (pHEMA). We hypothesize that samples with intermediate amounts of C18 ligand would allow albumin to recognize them and bind through its hydrophobic pockets specific for long chain fatty acids. Surface characterization has confirmed increasing amounts of C18 ligand on pHEMA as the percentage of C18 in solution increases, with maximum coverage achieved in 10% C18 samples. Adsorption from pure albumin solution revealed a small decrease in albumin adsorption from pHEMA to 1% C18 and 2.5% C18 samples, but on surfaces with 5% or higher C18 the amount of adsorbed albumin increased as the percentage of C18 increased. Competitive adsorption studies in the presence of both albumin and fibrinogen, and in the presence of all plasma proteins showed that 1% C18 and 2.5% C18 were the only surfaces selective for albumin, and that the presence of all plasma proteins may even potentiate albumin adsorption. Reversibility studies demonstrated that both 2.5% C18 and 5% C18 samples exchange 125I-albumin selectively in the presence of both unlabeled albumin and plasma, but 2.5% C18 samples presented higher exchangeability rates (58%). Clotting times using recalcified plasma revealed that samples with none or small amounts of C18 (pHEMA to 5% C18) did not shorten the clotting time compared to the negative control (polystyrene), indicating low activation of the intrinsic coagulation cascade. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.06.025PubMed ID: 19595453Language of Original Document: EnglishCorrespondence Address: Gonçalves, I.C.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: icastro@ineb.up.ptChemicals/CAS: fibrinogen, 9001-32-5; human serum albumin, 9048-49-1; polymacon, 25053-81-0, 25249-16-5, 98932-78-6; polystyrene, 9003-53-6; Biocompatible Materials; Coated Materials, Biocompatible; Hydrogels; Polyhydroxyethyl Methacrylate, 25249-16-5; Serum AlbuminReferences: Kottkemarchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the in vitro blood compatibility of dacron arterial prostheses (1989) Biomaterials, 10 (3), pp. 147-155;Ji, J., Feng, L.X., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin (2001) Biomaterials, 22 (22), pp. 3015-3023; Keogh, J.R., Eaton, J.W., Albumin-binding surfaces for biomaterials (1994) The Journal of Laboratory and Clinical Medicine, 124 (4), pp. 537-545; Keogh, J.R., Velander, F.F., Eaton, J.W., Albumin-binding surfaces for implantable devices (1992) Journal of Biomedical Materials Research, 26 (4), pp. 441-456; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., Albumin and fibrinogen adsorption on Cibacron blue F3G-A immobilised onto PU-PHEMA (polyurethane-poly(hydroxyethylmethacrylate)) surfaces (2003) Journal of Biomaterials Science Polymer Edition, 14 (5), pp. 439-455; McFarland, C.D., De Filippis, C., Jenkins, M., Tunstell, A., Rhodes, N.P., Williams, D.F., Albumin-binding surfaces: in vitro activity (1998) Journal of Biomaterials Science Polymer Edition, 9 (11), pp. 1227-1239; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Transactions American Society for Artificial Internal Organs, 27, pp. 499-503; Tsai, C.C., Huo, H.H., Kulkarni, P., Eberhart, R.C., Biocompatible coatings with high albumin affinity (1990) ASAIO Transactions, 36 (3), pp. 307-310; Wang, D.A., Chen, B.L., Ji, J., Feng, L.X., Selective adsorption of serum albumin on biomedical polyurethanes modified by a poly(ethylene oxide) coupling-polymer with Cibacron blue (F3G-A) endgroups (2002) Bioconjugate Chemistry, 13 (4), pp. 792-803; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Naeemi, E., Ratner, B.D., Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands (2009) Journal of Biomedical Materials Research Part A, 89 A (3), pp. 642-653; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) Journal of the American Chemical Society, 111 (1), pp. 321-335; Kwok, S.C., Mourad, P.D., Crum, L.A., Ratner, B.D., Surface modification of polymers with self-assembled molecular structures: multitechnique surface characterization (2000) Biomacromolecules, 1, pp. 139-148; Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-terminated self-assembled monolayers (2005) Biomaterials, 26 (18), pp. 3891-3899; Ratner, B.D., Hoffman, A.F., Schoen, F.J., Lemons, J.L., (2004) Biomaterials science - an introduction to materials in medicine. 2nd ed., , Elsevier Academic Press, San Diego, CA, USA; Ratner, B.D., Miller, I.F., Interaction of urea with poly(2-hydroxyethyl methacrylate) hydrogels (1972) Journal of Polymer Science Part a-1-Polymer Chemistry, 10 (8), pp. 2425-2445; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility testing, pp. 183-214. , Williams D.F. (Ed), Harcover: CRC Press; Cao, L., Chang, M., Lee, C.Y., Castner, D.G., Sukavaneshvar, S., Ratner, B.D., Plasma-deposited tetraglyme surfaces greatly reduce total blood protein adsorption, contact activation, platelet adhesion, platelet procoagulant activity, and in vitro thrombus deposition (2007) Journal of Biomedical Materials Research Part A, 81 (4), pp. 827-837; Stovbun, E.V., Kuzaev, A.I., Baturin, S.M., (1996) Polymer Science Series A, 38, pp. 691-695; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Yuu, K., Shiroya, T., Blood compatible aspects of poly(2-methoxyethylacrylate) (PMEA) - relationship between protein adsorption and platelet adhesion on PMEA surface (2000) Biomaterials, 21 (14), pp. 1471-1481; Castner, D.G., Ratner, B.D., Hirao, A., Nakahama, S., Characterization of poly(2-hydroxyethyl methacrylate) (PHEMA) by XPS (1996) Surface Science Spectra, 4 (1-4), p. 14; López, G.P., Ratner, B.D., Rapoza, R.J., Horbett, T.A., Plasma deposition of ultrathin films of poly(2-hydroxyethyl methacrylate): surface analysis and protein adsorption measurements (1993) Macromolecules, 26 (13), pp. 3247-3253; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., Albumin and fibrinogen adsorption on PU-PHEMA surfaces (2003) Biomaterials, 24 (12), pp. 2067-2076; Tsukagoshi, T., Kondo, Y., Yoshino, N., Protein adsorption on polymer-modified silica particle surface (2007) Colloids and Surfaces B Biointerfaces, 54 (1), pp. 101-107; Ratner, B.D., Biomedical applications of hydrogels: review and critical appraisal (1981) Biocompatibility of clinical implant materials, , Williams D.F. (Ed), CRC Press; Höök, F., Vörös, J., Rodahl, M., Kurrat, R., Böni, P., Ramsden, J.J., A comparative study of protein adsorption on titanium oxide surfaces using in situ ellipsometry, optical waveguide lightmode spectroscopy, and quartz crystal microbalance/dissipation (2002) Colloids and Surfaces B Biointerfaces, 24 (2), pp. 155-170; Stryer, L., (1998) Biochemistry. 4th ed., , WH Freeman, New York; Garrett, Q., Chatelier, R.C., Griesser, H.J., Milthorpe, B.K., Effect of charged groups on the adsorption and penetration of proteins onto and into carboxymethylated poly(HEMA) hydrogels (1998) Biomaterials, 19 (23), pp. 2175-2186; Mequanint, K., Sheardown, H., 2-Methacryloyloxyethyl N-butylcarbamate: a new co-monomer for synthesis of polyurethane hydrogels with improved mechanical properties for biomedical applications (2005) Journal of Biomaterials Science Polymer Edition, 16 (10), pp. 1303-1318; Horbett, T.A., Adsorption of proteins from plasma to a series of hydrophilic-hydrophobic copolymers. II. Compositional analysis with the prelabeled protein technique (1981) Journal of Biomedical Materials Research, 15 (5), pp. 673-695; Feng, L., Andrade, J.D., Protein adsorption on low-temperature isotropic carbon. 3. isotherms, competitivity, desorption and exchange of human albumin and fibrinogen (1994) Biomaterials, 15 (5), pp. 323-333; Pitt, W.G., Cooper, S.L., Albumin adsorption on alkyl chain derivatized polyurethanes. 1. The effect of C-18 alkylation (1988) Journal of Biomedical Materials Research, 22 (5), pp. 359-382; Markiewski, M.M., Nilsson, B., Ekdahl, K.N., Mollnes, T.E., Lambris, J.D., Complement and coagulation: strangers or partners in crime? (2007) Trends in Immunology, 28 (4), pp. 184-192; Zhang, Z., Zhang, M., Chen, S., Horbett, T.A., Ratner, B.D., Jiang, S., Blood compatibility of surfaces with superlow protein adsorption (2008) Biomaterials, 29 (32), pp. 4285-4291; Grunkemeier, J.M., Tsai, W.B., Horbett, T.A., Hemocompatibility of treated polystyrene substrates: contact activation, platelet adhesion, and procoagulant activity of adherent platelets (1998) Journal of Biomedical Materials Research, 41 (4), pp. 657-670; Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25 (26), pp. 5681-5703
Keywords: Adsorption; article; Biocompatible Materials; Biomaterials; blood clotting time; Blood Coagulation Tests; Body fluids; Clotting time; Coagulation; Coated Materials, Biocompatible; concentration response; controlled study; Fatty acids; fibrinogen; human serum albumin; hydrogel; Hydrogels; hydrophilicity; Ligands; long chain fatty acid; materials testing; Plasmas; PolyHEMA; Polyhydroxyethyl Methacrylate; polymacon; Polymer blends; polystyrene; Polystyrenes; priority journal; Protein adsorption; protein binding; Proteins; Serum Albumin; Surface modification; surface property; Surface treatment

The role of composition, morphology and crystalline structure in the electrochemical behaviour of TiN x thin films for dry electrode sensor materials - Cunha, L.T.; Pedrosa, P.; Tavares, C.J.; Alves, E.; Vaz, F.; Fonseca, C. (Electrochimica ActaElectrochim Acta, 2009)
A morphological, structural and electrochemical study of titanium nitride (TiN x) thin films, obtained by DC reactive sputtering on titanium substrates, was carried out for a wide range of compositions (0 < x < 1.34) aiming a selection of the best coatings for dry biomedical electrodes. The films displayed a columnar-type structure, with morphologies strongly dependent on the composition: a compact and smooth surface was found for the Ti-rich films, (x < 1), whereas the N-rich films, (x ≥ 1) displayed a rough and porous structure. The electrochemical study of the TiN x films was performed in synthetic sweat, aiming at simulating the contact with the skin. The voltammetric analysis showed anodic currents higher for TiN x films than for titanium for low and medium polarization potentials, whereas for potentials beyond 2 V the blocking behaviour of the TiN x films allowed them to display lower current values. The passive dissolution currents in the sub-μA/cm 2 range and the charge transfer resistances of the order of the MΩ proved the excellent stability of all films in sweat conditions. Finally, the electrochemical noise analysis showed that the near-stoichiometric and N-rich films display the lowest noise, being therefore the most suitable for electrode applications, where signals in the microvolt range, such as the electroencephalographic (EEG) signals, are to be monitored. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: ELCAAdoi: 10.1016/j.electacta.2009.08.004Language of Original Document: EnglishCorrespondence Address: Fonseca, C.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cfonseca@ineb.up.ptReferences: McAdams, E., Bioelectrodes (1988) Encyclopedia of Medical Devices and Instrumentation, p. 120. , Webster J.G. (Ed), Wiley, New York;Teplan, M., (2002) Meas. Sci. Rev., 2 (2); Searle, A., Kirkup, L., (2000) Physiolog. Meas., 22, p. 71; Ko, W.K., Hynecek, J., Dry electrodes and electrode amplifiers (1974) Biomedical Electrode Technology, , Miller H.A., and Harrison D.C. (Eds), Academic Press, N.Y; Fonseca, C., Vaz, F., Barbosa, M.A., (2004) Corros. Sci., 46 (12), p. 3005; Tallgren, P., Vanhatalo, S., Kaila, K., Voipio, J., (2005) Clin. Neurophysiol., 116, p. 799; Abd El Aal, (2008) Corros. Sci., 50, p. 41; Malik, H., Mgaloblishvili, R., Mills, B., (2004) J. Mat. Sci. Lett., 19 (19), p. 1779; Piscanec, S., Ciacchi, L., Vesselli, E., Comelli, G., Sbaizero, O., Meriani, S., De Vita, A., (2004) Acta Mater., 52, p. 1237; Gao, L., Gstöttner, J., Emling, R., Linsmeier, Ch., Wiltner, A., Hansch, W., Schmitt-Landsiedel, D., (2004) Microelectronic Eng., 76 (1-4), p. 76; Vaz, F., Ferreira, J., Ribeiro, E., Rebouta, L., Lanceros-Méndez, S., Mendes, J.A., Alves, E., de Rijk, J., (2005) Surf. Coat. Technol., 191, p. 317; Barradas, N.P., Jeynes, C., Webb, R.P., (1997) Appl. Phys. Lett., 71, p. 291; Ramos, A.R., Paúl, A., Rijniers, L., da Silva, M.F., Soares, J.C., (2002) Nucl. Instr. Meth., B190, p. 95; Randin, J.-O., (1988) J. Biomed. Mat. Res., 22, p. 649; Subramaniam, T.K., Srinivasulu Naidu, B., Uthanna, S., (1999) Cryst. Res. Technol., 34, p. 8; Rizzo, A., Signore, M.A., De Riccardis, M.F., Capodieci, L., Dimaio, D., Nocco, T., (2007) Thin Solid Films, 515, p. 6665; Sundgren, J.-E., Johansson, B.-O., Karlsson, S.-E., (1983) Thin Solid Films, 105, p. 353; Elstner, F., Ehrlich, A., Giegengack, H., Kupfer, H., Richter, F., (1994) J. Vac. Sci. Technol. A, 12, p. 476; Han, Z., Tian, J., Lai, Q., Yu, X., Li, G., (2003) Surf. Coat. Technol., 162, p. 189; Wriedt, H.A., Murray, J.L., Bull. Alloy Phase Diagrams (1987) 8/4, p. 378; Lu, K., Sui, M.L., Lück, R., (1994) Nanostruct. Mat., 4 (4), p. 465; Vaz, F., Machado, P., Rebouta, L., Cerqueira, P., Goudeau, Ph., Rivière, J.P., Alves, E., de Rijk, J., (2003) Surf. Coat. Technol., 174-175, p. 375; Norlin, A., Pan, J., Leygraf, C., (2005) J. Electrochem. Soc., 152 (2), pp. J7; Milosev, I., Strehblow, H., Navinsek, B., (1997) Thin Solid Films, 303, p. 246; Orazem, M., Tribollet, B., (2008) Electrochemical Impedance Spectroscopy, , John Wiley &Sons 233; Chappé, J.-M., Matin, N., Pearson, J., GTerwagne, J., Lintymer, J., Gavoille, J., Takadoum, (2004) Applied Suf. Sci., 222, p. 229; Logothetidis, S., Meletis, E., Stergioudis, G., Adjaottor, A., (1999) Thin Solid Films, p. 304; Huigen, E., Peper, A., Grimbergen, C., (2002) Med. Biol. Eng. Comput., 40, p. 332; Hladky, K., Dawson, J., (1982) Corrosion Sci., 22, p. 231
Keywords: Anodic currents; Bioelectric phenomena; Biomedical devices; biomedical electrodes; Blocking behaviour; Charge transfer; Charge transfer resistance; Chemical analysis; Crystalline structure; DC reactive sputtering; Dissolution; Dry electrode; EIS; Electrochemical behaviour; Electrochemical corrosion; Electrochemical electrodes; Electrochemical Noise Analysis; Electrochemical studies; Electroencephalographic signals; Ion exchange; morphology; Polarization potential; Porous structures; Selection of the best; Sensor materials; Smooth surface; Sputtering; Thin films; Titanium; Titanium nitride; Titanium substrates; Type structures; Voltammetric analysis

Role of vascular endothelial growth factor in the communication between human osteoprogenitors and endothelial cells - Grellier, M.; Ferreira-Tojais, N.; Bourget, C.; Bareillke, R.; Guillemot, F.; Amédée, J. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2009)
Proper bone remodeling requires an active process of angiogenesis which in turn supplies the necessary growth factors and stem cells. This tissue cooperation suggests a cross-talk between osteoblasts and endothelial cells. This work aims to identify the role of paracrine communication through vascular endothelial growth factor (VEGF) in co-culture between osteoblastic and endothelial cells. Through a well defined direct contact co-culture model between human osteoprogenitors (HOPs) and human umbilical vein endothelial cells (HUVECs), we observed that HUVECs were able to migrate along HOPs, inducing the formation of specific tubular-like structures. VEGF 165 gene expression was detected in the HOPs, was up-regulated in the co-cultured HOPs and both Fit-1 and KDR gene expression increased in co- cultured HUVECs. However, the cell rearrangement observed in co-culture was promoted by a combination of soluble chemoattractive factors and not by VEGF 165 alone. Despite having no observable effect on endothelial cell tubular-like formation, VEGF appeared to have a crucial role in osteoblastic differentiation since the inhibition of its receptors reduced the co-culture-stimulated osteoblastic phenotype. This co-culture system appears to enhance both primary angiogenesis events and osteoblastic differentiation, thus allowing for the development of new strategies in vascularized bone tissue engineering. © 2009 Wiley-Liss, Inc.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.22018Language of Original Document: EnglishCorrespondence Address: Grellier, M.; 146 Rue Leo Saignat, Zone Nord, Bat 4A, Case 45, F-33076 Bordeaux Cedex, France; email: maritie.grellier@inserm.frMolecular Sequence Numbers: GENBANK: AB021221, AF063657, AF063658, BC015690, BC021289, NM_000089;Chemicals/CAS: vasculotropin A, 489395-96-2; vasculotropin receptor, 301253-48-5; Receptors, Vascular Endothelial Growth Factor, EC 2.7.1.112; RNA, Messenger; Vascular Endothelial Growth Factor AReferences: Bordenave, L., Baquey, C., Bareille, R., Lefebvre, F., Lauroua, C., Guerin, V., Rouais, F., Anderson, J.M., Endothelial cell compatibility testing of three different Pellethanes (1993) J Biomed Mater Res, 27, pp. 1367-1381;Bouletreau, P.J., Warren, S.M., Spector, J.A., Peled, Z.M., Gerrets, R.P., Greenwald, J.A., Longaker, M.T., Hypoxia and VEGF up-regulate BMP-2 mRNA and protein expression in microvascular endothelial cells: Implications for fracture healing (2002) Plast Reconstr Surg, 109, pp. 2384-2397; Carano, R.A., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discov Today, 8, pp. 980-989; Carmeliet, P., Collen, D., Molecular basis of angiogenesis. Role of VEGF and VE-cadherin (2000) Ann NY Acad Sci, 902, pp. 249-262. , discussion 262-264; Clarkin, C.E., Emery, R.J., Pitsillides, A.A., Wheeler-Jones, C.P., Evaluation of VEGF-mediated signaling in primary human cells reveals a paracrine action for VEGF in osteoblast-mediated crosstalk to endothelial cells (2007) J Cell Physiol, 214, pp. 437-444; Cross, M.J., Claesson-Welsh, L., FGF and VEGF function in angiogenesis: Signalling pathways, biological responses and therapeutic inhibition (2001) Trends Pharmacol Sci, 22, pp. 201-207; Cross, M.J., Dixelius, J., Matsumoto, T., Claesson-Welsh, L., VEGF-receptor signal transduction (2003) Trends Biochem Sci, 28, pp. 488-494; Dallas, S.L., Rosser, J.L., Mundy, G.R., Bonewald, L.F., Proteolysis of latent transforming growth factor-beta (TGF-beta)-binding protein-1 by osteoclasts. A cellular mechanism for release of TGF-beta from bone matrix (2002) J Biol Chem, 277, pp. 21352-21360; Ferrara, N., Gerber, H.P., LeCouter, J., The biology of VEGF and its receptors (2003) Nat Med, 9, pp. 669-676; Fiedler, J., Leucht, F., Waltenberger, J., Dehio, C., Brenner, R.E., VEGF-A and P1GF-1 stimulate chemotactic migration of human mesenchymal progenitor cells (2005) Biochem Biophys Res Commun, 334, pp. 561-568; Gerber, H.P., Ferrara, N., Angiogenesis and bone growth (2000) Trends Cardiovasc Med, 10, pp. 223-228; Gerhardt, H., Golding, M., Fruttiger, M., Ruhrberg, C., Lundkvist, A., Abramsson, A., Jeltsch, M., Betsholtz, C., VEGF guides angiogenic sprouting utilizing endothelial tip cell filopodia (2003) J Cell Biol, 161, pp. 1163-1177; Guillotin, B., Bourget, C., Remy-Zolgadri, M., Bareille, R., Fernandez, P., Conrad, V., Amedee-Vilamitjana, J., Human primary endothelial cells stimulate human osteoprogenitor cell differentiation (2004) Cell Physiol Biochem, 14, pp. 325-332; Guillotin, B., Bareille, R., Bourget, C., Bordenave, L., Amedee, J., Interaction between human umbilical vein endothelial cells and human osteoprogenitors triggers pleiotropic effect that may support osteoblastic function (2008) Bone, 42, pp. 1080-1091; Jaffe, E.A., Culture of human endothelial cells (1980) Transplant Proc, 12, pp. 49-53; Lamalice, L., Le Boeuf, F., Huot, J., Endothelial cell migration during angiogenesis (2007) Circ Res, 100, pp. 782-794; Lampugnani, M.G., Orsenigo, F., Gagliani, M.C., Tacchetti, C., Dejana, E., Vascular endothelial cadherin controls VEGFR-2 internalization and signaling from intracellular compartments (2006) J Cell Biol, 174, pp. 593-604; Lebrin, F., Deckers, M., Bertolino, P., Ten Dijke, P., TGF-beta receptor function in the endothelium (2005) Cardiovasc Res, 65, pp. 599-608; Mayr-Wohlfart, U., Waltenberger, J., Hausser, H., Kessler, S., Gunther, K.P., Dehio, C., Puhl, W., Brenner, R.E., Vascular endothelial growth factor stimulates chemotactic migration of primary human osteoblasts (2002) Bone, 30, pp. 472-477; Miralem, T., Steinberg, R., Price, D., Avraham, H., VEGF(165) requires extracellular matrix components to induce mitogenic effects and migratory response in breast cancer cells (2001) Oncogene, 20, pp. 5511-5524; Neufeld, G., Cohen, T., Gengrinovitch, S., Poltorak, Z., Vascular endothelial growth factor (VEGF) and its receptors (1999) FASEB J, 13, pp. 9-22; Ortega, N., Behonick, D., Stickens, D., Werb, Z., How proteases regulate bone morphogenesis (2003) Ann NY Acad Sci, 995, pp. 109-116; Rousseau, S., Houle, F., Huot, J., Integrating the VEGF signals leading to actin-based motility in vascular endothelial cells (2000) Trends Cardiovasc Med, 10, pp. 321-327; Sorrell, J.M., Baber, M.A., Caplan, A., Human dermal fibroblast subpo- pulations; differential interactions with vascular endothelial cells in coculture: Nonsoluble factors in the extracellular matrix influence interactions (2008) Wound Repair Regen, 16, pp. 300-309; Street, J., Bao, M., deGuzman, L., Bunting, S., Peale Jr., F.V., Ferrara, N., Steinmetz, H., Filvaroff, E.H., Vascular endothelial growth factor stimulates bone repair by promoting angiogenesis and bone turnover (2002) Proc Natl Acad Sci USA, 99, pp. 9656-9661; Suarez, S., Ballmer-Hofer, K., VEGF transiently disrupts gap junctional communication in endothelial cells (2001) J Cell Sci, 114, pp. 1229-1235; Sun, L., Vitolo, M., Passaniti, A., Runt-related gene 2 in endothelial cells: Inducible expression and specific regulation of cell migration and invasion (2001) Cancer Res, 61, pp. 4994-5001; Unger, R.E., Sartoris, A., Peters, K., Motta, A., Migliaresi, C., Kunkel, M., Bulnheim, U., Kirkpatrick, C.J., Tissue-like self-assembly in cocultures of endothelial cells and osteoblasts and the formation of microcapillary-like structures on three-dimensional porous biomaterials (2007) Biomaterials, 28, pp. 3965-3976; Villars, F., Bordenave, L., Bareille, R., Amedee, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: Role of VEGF? (2000) J Cell Biochem, 79, pp. 672-685; Villars, F., Guillotin, B., Amedee, T., Dutoya, S., Bordenave, L., Bareille, R., Amedee, J., Effect of HUVEC on human osteoprogenitor cell differentiation needs heterotypic gap junction communication (2002) Am J Physiol Cell Physiol, 282, pp. C775-C785; Walker, D.L., Vacha, S.J., Kirby, M.L., Lo, C.W., Connexin43 deficiency causes dysregulation of coronary vasculogenesis (2005) Dev Biol, 284, pp. 479-498; Wang, H., Keiser, J.A., Vascular endothelial growth factor upregulates the expression of matrix metalloproteinases in vascular smooth muscle cells: Role of flt-1 (1998) Circ Res, 83, pp. 832-840; Wang, D.S., Miura, M., Demura, H., Sato, K., Anabolic effects of 1,25- dihydroxyvitamin D3 on osteoblasts are enhanced by vascular endothelial growth factor produced by osteoblasts and by growth factors produced by endothelial cells (1997) Endocrinology, 138, pp. 2953-2962; Xin, X., Yang, S., Ingle, G., Zlot, C., Rangell, L., Kowalski, J., Schwall, R., Gerritsen, M.E., Hepatocyte growth factor enhances vascular endothelial growth factor-induced angiogenesis in vitro and in vivo (2001) Am J Pathol, 158, pp. 1111-1120
Keywords: angiogenesis; article; Cell Communication; cell contact; Cell culture; cell differentiation; cell migration; cell motion; Cell Movement; Cells, Cultured; Co-culture; coculture; Coculture Techniques; controlled study; cytology; Endothelial Cells; endothelium cell; Enzyme Activation; gene expression; gene expression regulation; genetics; human; human cell; Human stem cells; human tissue; Humans; Humulus; messenger RNA; metabolism; Microscopy, Electron, Scanning; Migration; nucleotide sequence; osteoblast; Osteoblasts; Osteogenesis; paracrine signaling; phenotype; priority journal; Receptors, Vascular Endothelial Growth Factor; RNA, Messenger; Scanning electron microscopy; secretion; stem cell; umbilical cord; umbilical vein; upregulation; Vascular Endothelial Growth Factor A; vasculotropin 165; vasculotropin A; vasculotropin receptor; vasculotropin receptor 1; vasculotropin receptor 2; Vegf

Selective protein adsorption modulates platelet adhesion and activation to oligo(ethylene glycol)-terminated self-assembled monolayers with C18 ligands - Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Naeemi, E.; Ratner, B.D. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2009)
This study focuses on the selective binding of albumin to a nanostructured surfaces to inhibit other blood proteins from adsorbing thereby reducing platelet adhesion and activation. Tetra (ethylene-glycol)-terminated self- assembled monolayers (EG4 SAMs) with different percentages of CI 8 ligands on the surface were characterized by contact angle measurements, X-ray photoelectron microscopy, infrared reflection-absorption spectroscopy, and ellipsometry. A specific surface (2.5% C18 SAM) was found to be selective for human serum albumin (HSA) in the presence of both albumin and fibrinogen (HFG). The importance of this concentration of C18 ligands was stressed in reversibility studies since that surface exchanged almost all the preadsorbed HSA by HSA in solution, but not by HFG. The effect of protein adsorption in the subsequent adhesion and activation of platelets was studied by pre-immersing the surfaces in albumin and plasma before contact with platelets. Scanning electron microscopy and glutaraldehyde induced fluorescence technique images showed that as surfaces got more hydrophobic due to the immobilization of C18 ligands, the number of adherent platelets increased and their morphology changed from round to fully spread. Pre-immersion in HSA led to an 80°/o decrease in platelet adhesion and reduction of activation. Pre-immersion in 1% plasma was only relevant in 2.5% CI 8 SAMs since this was the only surface that demonstrated less adhesion of platelets comparing with buffer pre-immersion. However, they still adsorb more platelets then when HSA was preadsorbed. This was confirmed in competition studies between HSA and plasma that suggested that other plasma proteins were also adsorbing to this surface. © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 11Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32011PubMed ID: 18442116Language of Original Document: EnglishCorrespondence Address: Gonçalves, I. C.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Universidade do Porto, Run do Campo Alegre, 823, 4150-180 Porto, Portugal; email: icastro@ineb.up.ptChemicals/CAS: fibrinogen, 9001-32-5; glutaraldehyde, 111-30-8, 37245-61-7; human serum albumin, 9048-49-1; Carbon, 7440-44-0; Ethylene Glycol, 107-21-1; Ligands; Serum AlbuminReferences: Nath, N., Hyun, J., Ma, H., Chilkoti, A., Surface engineering strategies for control of protein and cell interactions (2004) Surf Sci, 570, pp. 98-110;Mao, C., Qiu, Y.Z., Sang, H.B., Mei, H., Zhu, A.P., Shen, J., Lin, S.C., Various approaches to modify biomaterial surfaces for improving hemocompatibility (2004) Adv Colloid Interface Sci, 110, pp. 5-17; Gorbet, M.B., Sefton, M.V., Biomaterial-associated thrombosis: Roles of coagulation factors, complement, platelets and leukocytes (2004) Biomaterials, 25, pp. 5681-5703; Kottkemarchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the in vitro blood compatibility of dacron arterial prostheses (1989) Biomaterials, 10, pp. 147-155; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Eberhart, R.C., Munro, M.S., Williams, G.B., Kulkarni, P.V., Shannon, W.A., Brink, B.E., Fry, W.J., Albumin adsorption and retention on C-18-alkyl-derivatized polyurethane vascular grafts (1987) Artif Organs, 11, pp. 375-382; Frautschi, J.R., Munro, M.S., Lloyd, D.R., Eberhart, R.C., Alkyl derivatized cellulose-acetate membranes with enhanced albumin affinity (1983) Trans Am Soc Artif Intern Organs, 29, pp. 242-244; Pitt WG, Cooper SL. Albumin adsorption on alkyl chain derivatized polyurethanes. I. The effect of C-18 alkylation. T Biomed Mater Res 1988;22:359-382Johnston, E., Ratner, B.D., Protein Adsorption: Friend or Foe? (1998) Immobilized biomolecules in analysis: A practical approach, pp. 79-94. , Cass T, Ligler FS, editors, Oxford: Oxford University Press;; Ji, J., Feng, L.X., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin (2001) Biomaterials, 22, pp. 3015-3023; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on cibacron blue F3G-A immobilized onto oligo (ethylene glycol)-terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14, pp. 945-954; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120, pp. 3464-3473; Palegrosdemange, C., Simon, E.S., Prime, K.L., Whitesides, G.M., Formation of self-assembled monolayers by chemisorption of derivatives of oligo(ethylene glycol) of structure Hs(Ch2)11 (Och2ch2)meta-Oh on gold (1991) J Am Chem Soc, 113, pp. 12-20; Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-ter- minated self-assembled monolayers (2005) Biomaterials, 26, pp. 3891-3899; Martins MCL, Ratner BD, Barbosa MA. Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolavers. I Biomed Mater Res 2003;67A: 158-171Owens, D.K., Wendt, R.C., Estimation of surface free energy of polymers (1969) J Appl Polym Sci, 13, pp. 1741-1747; Sousa, S.R., Moradas Ferreira, P., Saramago, B., Viseu Melo, L., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Sastry, M., A note on the use of ellipsometry for studying the kinetics of formation of self-assembled monolayers (2000) Bull Mater Sci, 23, pp. 159-163; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ralner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.G., Glutardialde- hyde induced fluorescence technique (GIFT): A new method for the imaging of platelet adhesion on biomaterials (2000) J Biomed Mater Res, 52, pp. 374-381; Herrwerth, S., Eck, W., Reinhardt, S., Grunze, M., Factors that determine the protein resistance of oligoether self-assembled monolayers-internal hydrophilicity, terminal hydrophilicity, and lateral packing density (2003) J Am Chem Soc, 125, pp. 9359-9366; Harder, P., Grunze, M., Dahint, R., Whitesides, G.M., Laibinis, P.E., Molecular conformation in oligo(ethylene glycol)-terminated self-assembled monolayers on gold and silver surfaces deter-mines their ability to resist protein adsorption (1998) J Phys Chem B, 102, pp. 426-436; Schwendel, D., Dahint, R., Herrwerth, S., Schloerholz, M., Eck, W., Grunze, M., Temperature dependence of the protein resistance of poly- and oligo(ethylene glycol)-terminated alkanethiolate monolayers (2001) Langmuir, 17, pp. 5717-5720; Zhu, B., Eurell, T., Gunawan, R., Leckband, D., Chain-length dependence of the protein and cell resistance of oligo(ethylene glycol)-terminated self-assembled monolayers on gold (2001) J Biomed Mater Res, 56, pp. 406-416; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (1999) J Biomed Mater Res, 49, pp. 435-447; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethio- lates on gold (2004) Biomaterials, 25, pp. 2557-2563
Keywords: Absorption spectroscopy; Acoustic microscopes; Adhesion; Adsorption; Albumin; Aldehydes; Angle measurement; article; Biological materials; Biomaterials; Blood Platelets; Blood protein; Blood substitutes; Carbon; Cell Shape; chemical composition; Concentration of; Contact angle; controlled study; Ethylene; Ethylene Glycol; ethylene glycol derivative; fibrinogen; Fluorescence technique; glutaraldehyde; gold nanoparticle; human; human serum albumin; Human serum albumins; Humans; hydrophobicity; Infrared reflection absorption spectroscopy; infrared spectroscopy; ligand; Ligands; Nanostructured surface; normal human; Oligo(ethylene glycol); Photoelectron spectroscopy; plasma; Plasma diagnostics; Plasma protein; Plasmas; Platelet adhesion; Platelet Adhesiveness; Platelets; Protein adsorption; protein binding; Proteins; Sams; Scanning electron microscopy; Selective binding; Selective protein adsorption; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Serum Albumin; Specific surface; Spectrophotometry, Infrared; Surface Properties; surface property; thrombocyte activation; thrombocyte adhesion; thrombocyte shape; X ray photoelectron spectroscopy; X-ray photoelectron microscopy

Sex differences in linear and complex fetal heart rate dynamics of normal and acidemic fetuses in the minutes preceding delivery - Bernardes, J.; Gonçalves, H.; Ayres-de-Campos, D.; Rocha, A.P. (Journal of Perinatal MedicineJ. Perinat. Med., 2009)
Aim: To assess linear and complex heart rate dynamics in relation to fetal gender in normal and acidemic fetuses during the minutes preceding delivery. Methods: Linear and non-linear fetal heart rate indices, namely mean FHR, long-term irregularity index, short-term variability, low and high frequency spectral indices, approximate and sample entropy, were assessed in 36 female and 30 male fetuses, adjusted for gestational age and weight, during the minutes preceding delivery. Analysis was performed in the initial and final minutes of each tracing in fetuses with umbilical artery blood pH at delivery ≥7.20, 7.11-7.19 and ≤7.10. Results: Progression of labor was associated with a significant decrease in non-linear indices and an increase in almost all linear indices, both in female and male fetuses, but changes were more marked in female fetuses. Non-acidemic females showed higher mean FHR in the final minutes of labor, compared with males. Acidemic females had higher linear indices when compared to similar male fetuses. Conclusions: During the minutes preceding delivery, female fetuses express higher linear indices than male fetuses, suggesting greater activation of the autonomic nervous system, while maintaining similar complexity indices, which suggests different reaction and adaptation capabilities to stress and distress. © 2009 by Walter de Gruyter.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2009.024PubMed ID: 19021459Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Faculdade de Medicina, Universidade Do Porto, Ginecologia e Obstetrícia, Al. Hernani Monteiro, Porto, 4200, Portugal; email: jbernardes59@gmail.comReferences: Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sà, J.P., Pereira-Leite, L., SisPorto 2.0 - a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto 3.5 - a central fetal monitoring station with online alerts based on computerized cardio-tocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-264; Beckers, F., Verheyden, B., Aubert, A.E., Aging and non-linear heart rate control in a healthy population (2006) Am J Physiol Heart Circ Physiol, 290, pp. H2560-H2570; Bekedam, D.J., Engelsbel, S., Mol, B.W., Buitendijk, S.E., van der Pal-de Bruin, K.M., Male predominance in fetal distress during labor (2002) Am J Obstet Gynecol, 187, pp. 1605-1607; Bennet, L., Booth, L.C., Ahmed-Nasef, N., Dean, J.M., Davidson, J., Quaedackers, J.S., Male disadvantage? Fetal sex and cardiovascular responses to asphyxia in preterm fetal sheep (2007) Am J Physiol Regul Integr Comp Physiol, 293, pp. R1280-R1286; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynaecol Obstet, 62, pp. 141-147; Bernardes, J., Gonçalves, H., Ayres-de-Campos, D., Rocha, A.P., Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states (2008) Early Hum Dev, 84, pp. 433-439; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grosssesse et de l'accouchement. (2004) Encyclopédie Médico- Chirurgicale, 148, pp. 1-10; Browner, W.S., Newman, T.B., Cummings, S.R., Hulley, S.B., (2001) Estimating sample size and power: The nitty-gritty, pp. 65-84. , Hulley SB, Cummings SR, Browner WS, Grady D, Hearst N, Newman TB, editors. Philadelphia: Lippincot Williams & Wilkins; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J Matern Fetal Invest, 8, pp. 23-26; Dawes, G.S., Moulden, M., Redman, C.W., Improvements in computerized fetal heart rate analysis antepartum (1996) J Perinat Med, 24, pp. 25-36; Dawes, N.W., Dawes, G.S., Moulden, M., Redman, C.W., Fetal heart rate patterns in term labor vary with sex, gestational age, epidural analgesia, and fetal weight (1999) Am J Obstet Gynecol, 180, pp. 181-187; DiPietro, J.A., Costigan, K.A., Shupe, A.K., Pressman, E.K., Johnson, T.R., Fetal neurobehavioral development: Associations with socioeconomic class and fetal sex (1998) Dev Psychobiol, 33, pp. 79-91; Dudewicz, E., Mishra, S., (1998) Modern mathematical statistics, , John Wiley and Sons, Inc; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin Sci (Lond), 92, pp. 345-349; Fusheng, Y., Bo, H., Qingyu, T., (1998) Approximate entropy and its application in biosignal analysis, 2, pp. 72-91. , editor. Nonlinear biomedical signal processing, Dynamical analysis and modelling. IEEE Press;; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Goncalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med Biol Eng Comput, 44, pp. 847-855; Goncalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum Dev, 83, pp. 585-591; Groome, L.J., Mooney, D.M., Holland, S.B., Smith, L.A., Atterbury, J.L., Dykman, R.A., Behavioral state affects heart rate response to low-intensity sound in human fetuses (1999) Early Hum Dev, 54, pp. 39-54; Ingemarsson, I., Herbst, A., Thorngren-Jerneck, K., Long-term outcome after umbilical artery acidemia at term birth: Influence of gender and duration of fetal heart rate abnormalities (1997) Br J Obstet Gynaecol, 104, pp. 1123-1127; Jensen-Urstad, K., Storck, N., Bouvier, F., Ericson, M., Lindblad, L.E., Jensen-Urstad, M., Heart rate variability in healthy subjects is related to age and gender (1997) Acta Physiol Scand, 160, pp. 235-241; King, T., Parer, J., The physiology of fetal heart rate patterns and perinatal asphyxia (2000) J Perinat Neonat Nurs, 14, pp. 19-39; Kuo, T.B., Yang, C.C., Sexual dimorphism in the complexity of cardiac pacemaker activity (2002) Am J Physiol Heart Circ Physiol, 283, pp. H1695-H1702; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) J Obstet Gynecol Reprod Biol, 114, pp. 137-143; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000, Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks, 3, pp. 637-641; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press;; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci USA, 88, pp. 2297-2301; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Ryan, S.M., Goldberger, A.L., Pincus, S.M., Mietus, J., Lipsitz, L.A., Gender- and age-related differences in heart rate dynamics: Are women more complex than men? (1994) J Am Coll Cardiol, 24, pp. 1700-1707; Sheiner, E., Hadar, A., Hallak, M., Katz, M., Mazor, M., Shoham-Vardi, I., Clinical significance of fetal heart rate tracings during the second stage of labor (2001) Obstet Gynecol, 97, pp. 747-752; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Transactions on Biomedical Engineering, 50, pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Välimäki, I.A., Rosén, K.G., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labor (2005) Br J Obstet Gynaecol, 112, pp. 418-423; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232;
Keywords: acidemia; Acidemic fetuses; article; autonomic nervous system; Birth Weight; blood pH; Cross-Sectional Studies; delivery; Delivery, Obstetric; entropy; Entropy and spectral analysis; Female; Fetal Heart; fetus; fetus heart rate; Gestational Age; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; Intrapartum; labor; Labor, Obstetric; male; Pregnancy; priority journal; Retrospective Studies; Sex Characteristics; sex difference; Umbilical Arteries; umbilical artery

Skin adhesive versus subcuticular suture for perineal skin repair after episiotomy - A randomized controlled trial - Mota, R.; Costa, F.; Amaral, A.; Oliveira, F.; Santos, C.C.; Ayres-de-Campos, D. (Acta Obstetricia et Gynecologica ScandinavicaActa Obstet. Gynecol. Scand., 2009)
Objective. Surgical repair of perineal lesions after delivery is frequently associated with pain and discomfort, interfering with the normal activities of the puerperium. The aim of this study was to compare perineal skin repair after episiotomy with adhesive glue versus a subcuticular suture, regarding the incidence of pain and wound complications. Study design. Randomized clinical trial. Setting. Tertiary care university hospital. Material and methods. One hundred women having mediolateral episiotomy at vaginal delivery were enrolled. They were randomized to receive skin adhesive (n = 53) or subcuticular suture (n = 47) for closure of perineal skin. The main outcome measure was self-evaluated pain in the 30 days following delivery. Secondary outcome measures were technical difficulties reported with the procedure, duration of surgical repair, wound complications observed at 42-68 hours post-partum and re-initiation of sexual activity by 30 days post-partum. Results. No significant differences were observed between the two groups in incidence of technical difficulties and failed procedures, pain during the procedure, wound complications at hospital discharge, self-evaluated measures of pain at 7 and 30 days or re-initiation of sexual activity by 30 days post-partum. The skin adhesive group had a significantly shorter mean duration of the procedure (four minutes less). Conclusion. Perineal skin closure using adhesive glue is faster than subcuticular suture, and associated with a similar incidence of complications and pain in the first 30 days.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: AOGSAdoi: 10.1080/00016340902883133Language of Original Document: EnglishCorrespondence Address: Mota, R.; Serviço de Ginecologia e Obstetrícia, Hospital de S. João, 4200-319 Porto, Portugal; email: sisporto@med.up.ptChemicals/CAS: Tissue Adhesives; cyanoacrylic acid octyl ester, 6701-17-3; polyglactin, 26780-50-7, 34346-01-5Tradenames: Dermabond, EthiconManufacturers: EthiconReferences: Kettle, C., Hills, R.K., Jones, P., Darby, L., Gray, R., Johanson, R., Continuous versus interrupted perineal repair with standard or rapidly absorbed sutures after spontaneous vaginal birth: A randomized controlled trial (2002) Lancet, 359, pp. 2217-2223;Gordon, B., Mackrodt, C., Fern, E., Truesdale, A., Ayers, S., Grant, A., The Ipswich Childbirth Study: 1. A randomized evaluation of two stage postpartum perineal repair leaving the skin unsutured (1998) Br J Obstet Gynaecol, 105, pp. 435-440; Mackrodt, C., Gordon, B., Fern, E., Ayers, S., Truesdale, A., Grant, A., The Ipswich Childbirth Study: 2. A randomized comparison of polyglactin 910 with chromic catgut for postpartum perineal repair (1998) Br J Obstet Gynaecol, 105, pp. 441-445; Kettle, C., Johanson, R.B., Continuous versus interrupted sutures for perineal repair (2000) Cochrane DataBase Syst Rev, (2). , CD000947; Kettle, C., Hills, R.K., Ismail, K.M.K., Continuous versus interrupted sutures for repair of episiotomy or second degree tears (2007) Cochrane DataBase Syst Rev, (4). , CD000947; Gemynthe, A., Langhoff-Roos, J., Sahl, S., Knudsen, J., New VICRYL formulation: An improved method of perineal repair? (1996) Br J Midwifery, 4, pp. 230-234; Oboro, V.O., Tabowei, T.O., Loto, O.M., Bosah, J.O., A multicentre evaluation of the two-layered repair of postpartum perineal trauma (2003) J Obstet Gynaecol, 23, pp. 5-8; Kindberg, S., Stehouwer, M., Hvidman, L., Henriksen, T.B., Postpartum perineal repair performed by midwives: A randomised trial comparing two suture techniques leaving the skin unsutured (2008) Br J Obstet Gynaecol, 115, pp. 472-479; Gennari, R., Rotmensz, N., Ballardini, B., Scevola, S., Perego, E., Zanini, V., A prospective, randomized, controlled clinical trial of tissue adhesive (2-octylcyanoacrylate) versus standard wound closure in breast surgery (2004) Surgery, 136, pp. 593-599; Bernard, L., Doyle, J., Friedlander, S.F., Eichenfield, L.F., Gibbs, N.F., Cunningham, B.B., A prospective comparison of octylcya-noacrylate tissue adhesive (dermabond) and suture for the closure of excisional wounds in children and adolescents (2001) Arch Dermatol, 137, pp. 1177-1180; Matin, S.F., Prospective randomized trial of skin adhesive versus sutures for closure of 217 laparoscopic port-site incisions (2003) J Am Coll Surg, 196, pp. 845-853; Bhende, S., Rothenburger, S., Spangler, D.J., Dito, M., In vitro assessment of microbial barrier properties of Dermabond( topical skin adhesive (2002) Surg Infect, 3, pp. 251-257; Rogerson, L., Mason, G.C., Roberts, A.C., Preliminary experience with twenty perineal repairs using Indermil tissue adhesive (2000) Eur J Obstet Gynecol Reprod Biol, 88, pp. 139-142; Bowen, M.L., Selinger, M., Episiotomy closure comparing enbucrilate tissue adhesive with conventional sutures (2002) Int J Gynecol Obstet, 78, pp. 201-205; Adoni, A., Anteby, E., The use of Histoacryl for the episiotomy repair (1991) Br J Obstet Gynaecol, 98, pp. 476-478; Man, J., Quinn, J., Cyanoacrylate tissue adhesives (1997) Am J Cosm Surg, 14, pp. 413-416; Maw, J.L., Quinn, J.V., Wells, G.A., Ducic, Y., Odell, P.F., Lamothe, A., A prospective comparison of octylcyanoacrylate tissue adhesive and suture for the closure of head and neck incisions (1997) J Otolaryngol, 26, pp. 26-30
Keywords: adult; article; clinical trial; comparative study; controlled clinical trial; controlled study; cyanoacrylic acid octyl ester; edema; episiotomy; Episiotomy closure; Female; granuloma; human; Humans; injury; major clinical study; obstetric care; pain; pain assessment; Perineal repair; perineum; perineum injury; polyglactin; priority journal; questionnaire; randomized controlled trial; sexual intercourse; Skin; Skin adhesive; suture; Suture Techniques; suturing method; Tissue adhesive; Tissue Adhesives; treatment outcome; vaginal delivery; wound closure; wound dehiscence; Wounds and Injuries

3-D biomodelling technology for maxillofacial reconstruction - Oliveira, M.; Sooraj Hussain, N.; Dias, A.G.; Lopes, M.A.; Azevedo, L.; Zenha, H.; Costa, H.; Santos, J.D. (Materials Science and Engineering CMater. Sci. Eng. C, 2008)
Biomodel is a product of rapid prototyping process that represents a new approach for surgical planning and simulation. Biomodels were found to be particularly effective to locate an exact defect with good measurement accuracy and without any risk to the patients' health. These models could provide surgeons a realistic impression of complex structures before surgical intervention, allowing a define diagnosis and a precise preoperative simulation of skeleton modifying interventions. This work reports on the application of innovative 3-D biomodelling technology in the maxillofacial reconstruction. This technology allows for the calculation of the exact contours, angulations, length and general morphology of iliac crest and fibula flaps for maxillofacial reconstruction in a total of 28 clinical cases. Clinical results have shown that by using this technique, much better facial symmetry and improved functionality were achieved after surgery, which resulted in enormous benefits for treated patients. © 2008 Elsevier B.V. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.msec.2008.02.007Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Pessa, J.E., (2001) Am. J. Orthod. Dentofac. Orthop., 119, p. 117;Poukens, J., Haex, J., Riediger, D., (2003) Comput. Aided Surg., 8 (3), p. 146; Brown, G.A., Milner, B., Firoozbakhsh, K., (2002) J. Orthop. Trauma, 16 (5), p. 347; Berry, E., Brown, J.M., Connell, M., Craven, C.M., Efford, N.D., Radjenovic, A., Smith, M.A., (1997) Med. Eng. Phys., 19 (1), p. 90; Urso, P.S.D., Barker, T.M., Earwaker, W.J., Bruce, L.J., Atkinson, R.L., Lanigan, M.W., Arvier, J.F., Effeney, D.J., (1999) J. Cranio-Maxillo-Facial Surg., 27, p. 30; Urso, P.S.D., Thompson, R.G., (1998) Aust. N.Z. J. Obstet. Gynaecol., 38, p. 205; Clair, J.J., (1996) J. Mater. Process. Technol., 57, p. 393; Pham, D.T., Gault, R.S., (1998) Int. J. Mach. Tools Manuf., 38, p. 1257; Onuh, S.O., Hon, K.K.B., (1998) Int. J. Mach. Tools Manuf., 38, p. 329; Barker, T.M., Earwaker, W.J., Lisle, D.A., (1994) Australas. Radiol., 38, p. 106; Peckitt, N.S., (1999) Br. J. Oral Maxillofac. Surg., 37, p. 353; Holck, D.E.E., Boyd Jr., E.M., Ng, J., Mauffray, R.O., B, (1999) Ophthalmology, 106, p. 1214; Pessa, J.E., Desvigne, L.D., Lambros, V.S., Nimerick, J., Sugunan, B., Zadoo, V.P., (1999) Aesthet. Plast. Surg., 23, p. 337; Gutierres, M., Dias, A.G., Lopes, M.A., Sooraj Hussain, N., Cabral, A.T., Almeida, L., Santos, J.D., (2007) J. Mater. Sci. Mater. Med., 18, p. 2377; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19 (1-3), p. 133; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci., Mater. Med., 10 (2), p. 111; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26 (28), p. 5609; Moroni, L., de Wijn, J.R., van Blitterswijk, C.A., (2006) Biomaterials, 27 (7), p. 974; Sanghera, B., Naique, S., Papaharilaou, Y., Amis, A., (2001) Rapid Prototyping J., 7 (5), p. 275; Pentecost, J.O., Icardo, J., Thornburg, K.L., (1999) Comput. Med. Imaging Graph., 23, p. 45; Urso, P.S.D., Atkinson, R.L., Lanigan, M.W., Earwaker, W.J., Bruce, L.J., Holmes, A., Barker, T.M., Thompson, RG., (1998) Br. J. Plast. Surg., 51, p. 522
Keywords: 3D Biomodelling; Biomodels; Complex structures; Concurrent engineering; Facial symmetries; Free flap designing; Health risks; Job analysis; Maxillofacial reconstruction; Measurement accuracies; New approaches; Process engineering; Prototyping processes; Rapid prototyping; Repair; Restoration; Surgical interventions; Surgical planning; Three dimensional

Automatic cell segmentation from confocal microscopy images of the Arabidopsis root - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Mendonça, A.M.; Campilho, A. (2008 5th IEEE International Symposium on Biomedical Imaging: From Nano to Macro, Proceedings, ISBIIEEE Int. Symp. Biomed. Imaging: Nano Macro, Proc., ISBI, 2008)
In vivo observation and tracking of cell division in the Arabidopsis thaliana root meristem, by time-lapse confocal microscopy, is central to biology research. The research herein described is based on large amount of image data, which must be analyzed to determine the location and state of cells. The possibility of automating the process of cell detection/marking is an important step to provide research tools to the biologists in order to ease the search for a special event as cell division. This paper discusses an automatic cell segmentation method, which selects the best cell candidates from a starting watershed based image segmentation. The selection of individual cells is obtained using a Support Vector Machine (SVM) classifier, based on the shape and edge strength of the cells' contour. The resulting segmentation is largely pruned of badly segmented cells, which can reduce the false positive detection of cell division. This is a good result on its own and a starting point for improvement of cell segmentation methodology. ©2008 IEEE.
Conference code: 73366Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusArt. No.: 4541095doi: 10.1109/ISBI.2008.4541095Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPPortugalReferences: Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res, 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A., Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo (2007) Motion07, pp. 13-13; Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of arabidopsis thaliana root meristem in confocal microscopy (2004) Proc. of the Inter. Conf. on Image Analysis and Recognition, pp. 166-174; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Trans. on PAMI, 7 (12), pp. 629-639; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Trans. on Image Processing, 16 (8), pp. 2080-2095. , August; Luc, V., Soille, P., Watersheds in digital spaces: An efficient algorithm based on immersion simulations IEEE Trans. on PAMI, 13 (6); Meyer, F., Beucher, S., Morphological segmentation (1990) JVCIR, 1 (1), pp. 21-46. , Sept; Bleau, A., Leon, L., Watershed-based segmentation and region merging (2000) Comput. Vis. Image Underst, 77 (3), pp. 317-370; Kovesi, P., Symmetry and asymmetry from local phase (1997) Proc. of the Tenth Australian Joint Conf. on Artificial Intelligence, , December; Burges, C., A tutorial on support vector machines for pattern recognition (1998) Data Mining and Knowledge Discovery, 2 (2), pp. 121-167 Sponsors: Institute of Electrical and Electronic Engineers; Engineering in Medicine and Biology Society; Signal Processing Society
Keywords: Biological cells; Biomedical image processing; Cell divisions; cell proliferation; Cell segmentation; Cells; confocal microscopy; image processing; Image segmentation; Microscopic examination; Support vector machines; Technical presentations

Biocompatibility evaluation of DLC-coated Si 3N 4 substrates for biomedical applications - Salgueiredo, E.; Vila, M.; Silva, M.A.; Lopes, M.A.; Santos, J.D.; Costa, F.M.; Silva, R.F.; Gomes, P.S.; Fernandes, M.H. (Diamond and Related MaterialsDiamond Relat. Mat., 2008)
DLC coatings are of enormous interest for biotribological applications due to their biocompatibility, auto-lubricious, and non-stick properties. The most demanding implant is the hip joint. Alternative materials to metal alloys are being increasingly investigated aiming low wear debris volume, in any case innocuous wear particles. Silicon nitride (Si 3N 4) ceramics are light, tough, mechanical resistant, inert materials, turning them suitable for high-load medical applications. In this study, Si 3N 4 polished substrates were coated with adherent DLC coatings grown by DC magnetron sputtering to reduce of the friction forces against any antagonist material. Surface characterization results showed that the developed material is quite hydrophobic, with a total surface tension of 45.7 mN/m (polar component: 9.1 mN/m; dispersive component: 36.6 mN/m), and a zeta potential of - 35.0 ± 1.3 mV. In vitro testing using an acellular simulated body fluid (SBF) showed no apatite layer formation ability, as confirmed by SEM observation and analysis of the solution ions concentration with immersion time. MG63 osteoblast-like cells showed poor adhesion on the DLC films but the adherent cells displayed a normal morphology and, as compared to standard polystyrene tissue culture plates, exhibited a higher cell growth rate, suggesting no indication of cytotoxicity. Results suggested that the novel DLC-coated Si 3N 4 biomaterial should be adequate to be used for articular prostheses medical application. © 2007 Elsevier B.V. All rights reserved.
Cited By (since 1996): 30Export Date: 21 November 2012Source: ScopusCODEN: DRMTEdoi: 10.1016/j.diamond.2007.08.019Language of Original Document: EnglishCorrespondence Address: Silva, R.F.; CICECO, Glass and Ceramics Eng. Department, University of Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@cv.ua.ptReferences: Sargeant, A., Goswami, T., (2006) Mater. Des., 27, p. 287;Petzow, G., Herrmann, M., (2002) Structure and Bonding, 102, p. 47. , Janson M. (Ed), Springer-Verlag, Berlin; Narayan, R.J., (2005) Mater. Sci. Eng., C, Biomin. Mater., Sens. Syst., 25, p. 405; Cui, F.Z., Li, D.J., (2000) Surf. Coat. Technol., 131, p. 481; Zhao, Q., Liu, Y., Abel, E.W., (2004) J. Colloid Interface Sci., 280, p. 174; Vila, M., Abreu, C.S., Salgueiredo, E., Almeida, F.A., Fernandes, A.J.S., Costa, F.M., Gomes, J.R., Silva, R.F., (2006) Thin Solid Films, 515, p. 2192; Fairbrother, F., Mastin, H., (1924) J. Chem. Soc., 75, p. 2318; Owens, D.K., Wendt, R.D., (1969) J. Appl. Polym. Sci., 13, p. 1741; Kokubo, T., Takadama, H., (2006) Biomaterials, 27, p. 2907; Strom, G., Fredriksson, M., Stenius, P., (1987) J. Colloid Interface Sci., 119, p. 352; Schulz, H., Leonhardt, M., Scheibe, H.J., Schultrich, B., (2005) Surf. Coat. Technol., 200, p. 1123; Wilson, C.J., (2005) Tissue Eng., 11, p. 1; Haynes, C.A., Norde, W., (1994) Colloids Surf., B Biointerfaces, 2, p. 517; Shelton, R.M., Rasmussen, A.C., Davies, J.E., (1988) Biomaterials, 9, p. 24; Davies, J.E., Causton, B., Bovell, Y., Davy, K., Sturt, C.S., (1986) Biomaterials, 7, p. 231; Dearnaley, G., Arps, J.H., (2005) Surf. Coat. Technol., 200, p. 2518
Keywords: Biocompatibility; Biomedical applications; Cell cultures; Coatings; Diamond like carbon films; DLC coatings; Hip joint; hydrophobicity; Magnetron sputtering; Medical applications; Metal alloys; Simulated body fluid (SBF); Tribology; Wear of materials

Biocompatibility of highly macroporous ceramic scaffolds: Cell adhesion and morphology studies - Teixeira, S.; Ferraz, M.P.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2008)
Hydroxyapatite porous scaffolds can be used for tissue engineering applications since they can serve as templates for cell adhesion, proliferation and ultimately for tissue repair. One way to address this issue is to evaluate the cell adhesion using several characterization techniques namely, cytotoxicity assays and cell visualization. On the other hand, when using highly macroporous scaffolds some techniques may not be adequate for evaluation, such as MTT. In this work, cytotoxicity assay (MTS), scanning electron microscopy (SEM) and Confocal laser scanning microscopy (CLSM) were used to evaluate cell adhesion in highly macroporous hydroxyapatite scaffolds. It was possible to observe that some techniques were not suitable to evaluate cell adhesion. In addition, it was shown that for this kind of scaffolds, confocal laser scanning microscopy is a powerful tool for cell adhesion and proliferation evaluation. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3005-xPubMed ID: 17665126Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: smsilva@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Biocompatible Materials; Ceramics; Durapatite, 1306-06-5References: Jones, A.C., (2004) Biomaterials, 25, p. 4947;Karaggeorgiou, V., (2005) Biomaterials, 27, p. 5474; Leon, C.A., Leon, Y., (1998) Adv. Colloid. Interface Sci., 76-77, p. 341; Kuboki, Y., Takita, H., Kobayashi, D., Tsuruga, E., Inoue, M., Murata, M., (1998) J. Biomed. Mater. Res., 39, p. 190. , 2; Heise, U., Osborn, J.F., Duwe, F., (1990) Int. Orthop., 14, p. 329; Bucholz, R.W., Carlton, A., Holmes, R.E., (1987) Orthop. Clin. North. Am., 18, p. 323; Hill, P.A., (1998) Br. J. Orthod., 25, p. 101; Martin, R.B., (1999) Mater. Sci. Forum, 293, p. 5; Nunes, C.R., Simske, S.J., Sachdeva, R., Wolford, L.M., (1997) J. Biomed. Mater. Res., 36, p. 560; Queiroz, A.C., Teixeira, S., Monteiro, F.J., Santos, J.D., (2004) Key Eng. Mater., 254-256, p. 997; Queiroz, A.C., Teixeira, S., Monteiro, F.J., Santos, J.D., (2004) Mater. Sci. Forum, 455-456, p. 358; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Porous, H.A., (2005) Key Eng. Mater., 284-286; Teixeira, S.M., Queiroz, A.C., Monteiro, F.J., Ferraz, M.P., In vitro analysis of macroporous ceramic matrices: Preliminary results (2005) 19th European Conference on Biomaterials, , PP-P173; Naples, Italy, Sept 11-15
Keywords: article; Bioassay; Biocompatibility; Biocompatible Materials; cell adhesion; Cell Line, Tumor; cell proliferation; cell structure; Ceramic materials; ceramics; confocal laser microscopy; controlled study; Cytotoxicity; Cytotoxicity assay; Durapatite; human; human cell; Humans; hydroxyapatite; Macroporous ceramic scaffolds; Microscopy, Confocal; Microscopy, Electron, Scanning; Osteoblasts; priority journal; Scanning electron microscopy; Tissue engineering; Tissue Scaffolds

Biodegradable chitosan-silicate porous hybrids for drug delivery - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A. (Key Engineering MaterialsKey Eng Mat, 2008)
Porous chitosan-silicate hybrids were prepared by freeze-drying the precursor sol solutions synthesized from chitosan and 3- glycidoxypropyltrimethoxysilane (GPTMS). Degradability of and the release of cytochrome C in to phosphate buffer saline solution (PBS) were examined as a function of the GPTMS content. The hybrids were less degradable with larger GPTMS contents, and the cytochrome C release profile was so controllable as to give either burst release or slow one due to the GPTMS content. Thus, the present porous chitosan-silicate hybrids were considered applicable to drug delivery systems.
Keywords: biodegradability; Buffer saline solution; chitosan; Chitosan silicate hybrid; Chitosan-silicate hybrid; Drug delivery; Porous materials; Proteins; Silicates; Synthesis (chemical)

Bone ingrowth in macroporous Bonelike ® for orthopaedic applications - Gutierres, M.; Lopes, M.A.; Sooraj Hussain, N.; Lemos, A.F.; Ferreira, J.M.F.; Afonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Acta BiomaterialiaActa Biomater., 2008)
The aim of this study was to evaluate the biological behaviour of porous scaffold structures of Bonelike ® which is suitable for either direct clinical use or tissue engineering applications. Porous cylindrical specimens 8 × 10 mm were implanted in the lateral aspect of the tibia of 13 patients (mean age 54 years), during osteotomy surgery for the treatment of medial compartment osteoarthritis of the knee. Implanted cylinders were retrieved at the same time as the removal of the blade plates at 3, 6, 9 and 12 months. Scanning electron microscopy and histological evaluations were performed to observe the biological responses of human bone tissue to porous Bonelike ®. The penetration depth was determined for all implantation periods, and after 6 months it was already possible to see new bone in the centre of the implanted cylinders, which gives 100% of penetration depth for all implantations periods except for 3 months when bone could only be seen in the peripherical region. Regarding the percentage of the area covered by new bone calculated from two-dimensional histological sections, values of 53 ± 15, 76 ± 12 and 88 ± 9% were achieved for 6, 9 and 12 months, respectively. Due to its structural features porous Bonelike ® permitted effective vascularization and bone ingrowth, and therefore was fully osteointegrated as shown in the histological surveys. A slow biomaterial degradation with implantation time is envisaged since the material has displayed surface degradation. Bonelike ® scaffolds show potential for complete ingrowth of osseous tissue and restoration of vascularization throughout the defected site. © 2007.
Cited By (since 1996): 13Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.06.009PubMed ID: 17716960Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; FEUP - Faculdade de Engenharia, Universidade do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: BonelikeReferences: Akamatsu, Y., Koshino, T., Saito, T., Wada, J., Changes in osteosclerosis of the osteoarthritic knee after high tibial osteotomy (1997) Clin Orthop, 334, pp. 207-214;Coventry, M.B., Ilstrup, D.M., Wallrichs, S.L., Proximal tibial osteotomy. A critical long-term study of eighty-seven cases (1993) J Bone Joint Surg, 75 -A, pp. 196-201; Hernigou, P., Medevielle, D., Debeyre, J., Goutallier, D., Proximal tibial osteotomy for osteoarthritis with varus deformity. A ten to thirteen-year follow-up study (1987) J Bone Joint Surg Am, 69, pp. 332-354; Hernigou, P., Ma, W., Open wedge tibial osteotomy with acrylic bone cement as bone substitute (2001) Knee, 8, pp. 103-110; Koshino, T., Murase, T., Saito, T., Medial opening-wedge high tibial osteotomy with use of porous hydroxyapatite to treat medial compartment osteoarthritis of the knee (2003) J Bone Joint Surg Am, 85, pp. 78-85; Simske SJ, Ayers RA, Bateman TA. Porous Materials for Bone Engineered. In: Materials Science Forum. Zurich: Trans Tech Publications; 1997. Vol. 250, pp. 151-182Hing, K.A., Bone repair in the twenty-first century: biology, chemistry or engineering? (2004) Philos Trans A Math Phys Eng Sci, 362 (1825), pp. 2821-2850; Hui, P.W., Leung, P.C., Sher, A., Fluid conductance of cancellous bone graft as a predictor for graft-host interface healing (1996) J Biomech, 29 (1), pp. 123-132; Ben-Nissan, B., Natural bioceramics: from coral to bone and beyond (2003) Curr Opin Solid State Mater Sci, 7 (4-5), p. 283; Shors, E.C., Holmes, R.E., Porous hydroxyapatite (1993) Introduction to Biomaterials, pp. 181-198. , Hench L.L., and Wilson J. (Eds), World Scientific, Singapore; Prado da Silva, M.H., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., Porous glass reinforced hydroxyapatite materials produced with different organic additives (2002) J Non-Cryst Solids, 304, pp. 286-292; Prado da Silva, M.H., Lemos, A.F., Ferreira, J.M.F., Lopes, M.A., Santos, J.D., Production of porous biomaterials based on glass reinforced hydroxyapatite composites (2002) Key Eng Mater, 230-232, pp. 483-486; Rocha, J., Lemos, A., Agathopoulos, S., Valério, P., Kannan, S., Oktar, F., Scaffolds for bone restoration from cuttlefish (2005) Bone, 37 (6), pp. 850-857; Sepulveda, P., Binner, J.G.P., Processing of cellular ceramics by foaming and in situ polymerization of organic monomers (1999) J Eur Ceram Soc, 19 (12), pp. 2059-2066; Ozgur Engin, N., Cuneyt Tas, A., Manufacture of macroporous calcium hydroxyapatite bioceramics (1999) J Eur Ceram Soc, 19 (13-14), pp. 2569-2572; Peng, H.X., Fan, Z., Evans, J.R.G., Busfield, J.J.C., Microstructure of ceramic foams (2000) J Eur Ceram Soc, 20 (7), pp. 807-813; Komlev Vladimir, S., Barinov Serguei, M., Koplik Elena, V., A method to fabricate porous spherical hydroxyapatite granules intended for time-controlled drug release (2002) Biomaterials, 23 (16), pp. 3449-3454; Milosevski, M., Bossert, J., Milosevski, D., Gruevska, N., Preparation and properties of dense and porous calcium phosphate (1999) Ceram Int, 25, pp. 693-696; Tadic, D., Beckmann, F., Schwarz, K., Epple, M., A novel method to produce hydroxyapatite objects with interconnecting porosity that avoids sintering (2004) Biomaterials, 25, pp. 3335-3340; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of the suspensions (2004) Mater Sci Forum, 455-456, pp. 361-365; Lemos, A.F., Ferreira, J.M.F., Porous bioactive calcium carbonate implants processed by starch consolidation (2000) J Mat Sci Eng C, C11, pp. 35-40; Lemos, A.F., Ferreira, J.M.F., Combining foaming and starch consolidation methods to develop macroporous HA implants (2004) Key Eng Mater, 254-256, pp. 1041-1044; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., New method for the incorporation of soluble bioactive glasses to reinforce porous HA structures (2004) Key Eng Mater, 254-256, pp. 1033-1036; Gauthiera, O., Boulerb, J.M., Aguadoa, E., Piletb, P., Daculsi, G., Macroporous biphasic calcium phosphate ceramics: influence of macropore diameter and macroporosity percentage on bone ingrowth (1998) Biomaterials, 19, pp. 133-139; Hing, A.K., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Mediation of bone ingrowth in porous hydroxyapatite bone graft substitutes (2004) J Biomed Mater Res, 68 A, pp. 187-200; Rubin, P.A., Popham, J.K., Bilyk, J.R., Shore, J.W., Comparison of fibrovascular ingrowth into hydroxyapatite and porous polyethylene orbital implants (1994) Ophthal Plast Reconstr Surg, 10 (2), pp. 96-103; Hing, K.A., Annaz, B., Saeed, S., Revell, P.A., Buckland, T., Microporosity enhances bioactivity of synthetic bone graft substitutes (2005) J Mater Sci: Mater Med, 16, pp. 467-475; Klawitter, J.J., Bagwell, J.G., Weinstein, A.M., Sauer, B.W., An evaluation of bone growth into porous high density polyethylene (1976) J Biomed Mater Res, 10 (2), pp. 311-323; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Quantification of bone ingrowth within bone-derived porous hydroxyapatite implants of varying density (1999) J Mater Sci: Mater Med, 10, pp. 663-670; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Biomechanical assessment of bone ingrowth in porous hydroxyapatite (1997) J Mater Sci: Mater Med, 8, pp. 731-736; Ayers, R.A., Wolford, L.M., Bateman, T.A., Ferguson, V.L., Simske, S.J., Quantification of bone ingrowth into porous block hydroxyapatite in humans (1999) J Biomed Mater Res, 47, pp. 54-59; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Role of interconnections in porous bioceramics on bone recolonization in vitro and in vivo (1999) J Mater Sci: Mater Med, 10 (2), pp. 111-120; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with two different pore size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic study of bony ingrowth and implant substitution (1988) Clin Orthop Relat Res, 232, pp. 127-138; Kuhne, J.H., Bartl, R., Frisch, B., Hammer, C., Jansson, V., Zimmer, M., Bone formation in coralline hydroxyapatite. Effects of pore size studied in rabbits (1994) Acta Orthop Scand, 65 (3), pp. 246-252; Holmes, R., Mooney, V., Bucholz, R., Tencer, A., A coralline hydroxyapatite bone graft substitute. Preliminary report (1984) Clin Orthop Relat Res, 188, pp. 252-262; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21 (18), pp. 1905-1910; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Santos JD, Hastings G, Knowles JC. Sintered hydroxyapatite compositions and method for the preparation thereof. Worldwide Application (PCT), Patent No. 1 189 851, 1999Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20 (21), pp. 2085-2090; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48 (5), pp. 734-740; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, Surface tension and Zeta potential measurements of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and Indirect effects of P 2O 5 - glass reinforced - hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibiae of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and Double layer HA-P 2O 5/CaO Glass coatings: influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 12, pp. 629-638; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Biological behaviour of Bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 17, pp. 1041-1044; Duarte, F., Santos, J.D., Afonso, A., Medical applications of Bonelike ® in maxillofacial surgery (2004) Adv Mater Forum, pp. 370-373; Lobato, J.V., Hussain, N.S., Botelho, C.M., Titanium dental implants coated with Bonelike ®: clinical case report (2006) Thin Solid Films, 515, p. 279; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: a preliminary report (1965) J Bone Joint Surg Am, 47, pp. 984-990; Coventry, M.B., Upper tibia osteotomy for gonarthrosis. The evolution of the operation in the last 18 years and long term results (1979) Orthop Clin North Am, 10, pp. 191-210; Coventry, M.B., Current concepts review. Upper tibia osteotomy for osteoarthritis (1985) J Bone Joint Surg Am, 67 A, pp. 1136-1140
Keywords: adult; aged; article; biomaterial; bone defect; Bone graft; bone growth; Bone Regeneration; Bone Substitutes; bone tissue; Bonelike; clinical article; controlled study; Female; histology; human; human tissue; Humans; implant; knee osteoarthritis; male; materials testing; Microscopy, Electron, Scanning; Middle Aged; molecular scaffold; Orthopaedic; orthopedics; Osseointegration; Osteoarthritis; osteotomy; porosity; Porous materials; priority journal; Prostheses and Implants; Scanning electron microscopy; tibia; Time Factors; Tissue engineering; tissue section; vascularization; ®

Cell-induced response by tetracyclines on human bone marrow colonized hydroxyapatite and Bonelike ® - Gomes, P.S.; Santos, J.D.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2008)
Semi-synthetic tetracyclines are commonly used antibiotics that also seem to play an important role in the modulation of the immuno-inflammatory imbalance, verified in several bone diseases. The association of a therapeutic agent (that prevents bacterial infection and induces tissue formation) to a biomaterial aiming to repair/regenerate bone defects could contribute to a more predictable clinical outcome. The present study intends to evaluate the proliferation and functional activity of osteoblast-induced human bone marrow cells, cultured on the surface of hydroxyapatite (HA) and Bonelike ®, in the presence of therapeutic concentrations of doxycycline and minocycline. First passage bone marrow cells were cultured for 35 days on the surface of HA and Bonelike ® discs, in the absence or presence of 1 μg ml
Cited By (since 1996): 9Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.12.006PubMed ID: 18291737Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Laboratório de Farmacologia e Biocompatibilidade Celular, Faculdade de Medicina Dentária, Universidade do Porto (FMDUP), Rua Dr. Manuel Pereira da Silva, s/n, 4200-392 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; doxycycline, 10592-13-9, 17086-28-1, 564-25-0; hydroxyapatite, 1306-06-5, 51198-94-8; minocycline, 10118-90-8, 11006-27-2, 13614-98-7; Alkaline Phosphatase, EC 3.1.3.1; Bone Substitutes; Calcium, 7440-70-2; Culture Media; Durapatite, 1306-06-5; Minerals; Tetracycline, 60-54-8Tradenames: BonelikeReferences: Chambers, H., Protein synthesis inhibitors and miscellaneous antibacterial agents (2006) Goodman and Gilman's - The Pharmacological Basis of Therapeutics, pp. 1173-1202. , Brunton L. (Ed), McGraw-Hill, Germany;Alkan, A., Erdem, E., Gunhan, O., Karasu, C., Histomorphometric evaluation of the effect of doxycycline on the healing of bone defects in experimental diabetes mellitus: a pilot study (2002) J Oral Maxillofac Surg, 60, p. 898; Buchter, A., Kleinheinz, J., Meyer, U., Joos, U., Treatment of severe peri-implant bone loss using autogenous bone and a bioabsorbable polymer that delivered doxycycline (Atridox TM) (2004) Brit J Oral Maxillofacial Surg, 42, pp. 452-456; Ramamurthy, N., Rifkin, B., Greenwald, R., Xu, J.-W., Liu, Y., Turner, G., Inhibition of matrix metalloproteinase-mediated periodontal bone loss in rats: a comparison of 6 chemically modified tetracyclines (2005) J Periodontol, 73, pp. 726-734; Golub, L., Ramamurthy, N., Kaneko, H., Sasaki, T., Rifkin, B., McNamara, T., Tetracycline administration prevents diabetes-induced osteopenia in the rat: initial observations (1990) Res Commun Chem Pathol Pharmacol, 68, p. 27; Williams, S., Wakisaka, A., Zeng, Q., Barnes, J., Martin, G., Wechter, W., Minocycline prevents the decrease in bone mineral density and trabecular bone in ovariectomized aged rats (1996) Bone, 19, pp. 637-644; Williams, S., Wakisaka, A., Zeng, Q., Barnes, J., Seyedin, S., Martin, G., Effect of minocycline on osteoporosis (1998) Adv Dental Res, 12, pp. 71-75; Pytlik, M., Folwarczna, J., Janiec, W., Effects of doxycycline on mechanical properties of bones in rats with ovariectomy-induced osteopenia (2004) Calcified Tissue Int, 75, pp. 225-230; Holmes, S., Still, K., Buttle, D., Bishop, N., Grabowski, P., Chemically modified tetracyclines act through multiple mechanisms directly on osteoclast precursors (2004) Bone, 35, pp. 471-478; Polson, A., Bouwsma, O., McNamara, T., Golub, L., Enhancement of alveolar bone formation after tetracycline administration in squirrel monkeys (2005) J Appl Res Clin Dent, pp. 32-42; Yamaguchi, A., Udagawa, T., Sawai, T., Transport of divalent cations with tetracycline as mediated by the transposon Tn10-encoded tetracycline resistance protein (1990) J Biol Chem, 265, pp. 4809-4813; Li, S., de Wijn, J., Layrolle, P., de Groot, K., Synthesis of macroporous hydroxyapatite scaffolds for bone tissue engineering (2002) J Biomed Mater Res, 61, pp. 109-120; Giannoudis, P., Dinopoulos, H., Tsiridis, E., Bone substitutes: an update (2005) Int J Care Injured, 365, p. 220; LeGeros, R., Properties of osteoconductive biomaterials: calcium phosphates (2002) Clin Orthop, 395, pp. 81-98; Suchanek, W., Yoshimura, M., Processing and properties of hydroxyapatite-based biomaterials for use as hard tissue replacement implants (1998) J Mater Res, 13, pp. 94-117; Lopes, M., Santos, J., Monteiro, F., Knowles, J., Glass reinforced hydroxyapatite: a comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-250; Hench, L., Bioactive materials: the potential for tissue regeneration (1998) J Biomed Mater Res, 41, pp. 511-518; Kellomaki, M., Niiranen, H., Puumanen, K.A.N., Waris, T., Tormala, P., Bioabsorbable scaffolds for guided bone, regeneration, and generation (2000) Biomaterials, 21, pp. 2495-2505; Santos, J., Reis, R., Monteiro, F., Knowles, J., Hastings, G., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions structure and properties of the composites (1995) J Mater Sci Mat Med, 6, p. 348; Santos, J., Silva, P., Knowles, J., Talal, S., Monteiro, F., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO (1996) J Mater Sci Mat Med., 7, p. 187; Duarte, F., Santos, J., Afonso, A., Medical applications of Bonelike in maxillofacial surgery (2004) Mater Sci Forum, 370, pp. 455-456; Gutierres, M., Hussain, N., Afonso, A., Almeida, L., Cabral, A., Lopes, M., Biological behaviour of bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 1041, pp. 284-286; Brause, B., Infections with prostheses in bones and joints (2000) Mandell, Douglas and Bennett's Principles and Practice of Infectious Diseases. 5th ed., pp. 1196-1200. , Mandell G., Bennet J., and Dolin R. (Eds), Churchill Livingstone, Philadelphia; Darley, E., MacGowan, A., Antibiotic treatment of Gram-positive bone and joint infections (2004) J Antimicrobial Chemotherapy, 53, pp. 928-935; Zucchelli, G., Sforza, N., Clauser, C., Cesari, C., De Sanctis, M., Topical and systemic antimicrobial therapy in guided tissue regeneration (1999) J Periodontol, 70, pp. 239-247; Yukna, R., Sepe, W., Clinical evaluation of localized periodontosis defects treated with freeze-dried bone allografts combined with local and systemic tetracyclines (1982) Int J Periodontics Restorative Dent, 2, pp. 8-21; Shirtliff, M., Mader, J., Acute septic arthritis (2002) Clin Microbiol Rev, 15, pp. 527-544; Sunder, M., Babu, N., Victor, S., Kumar, K., Kumar, T., Biphasic calcium phosphates for antibiotic release (2005) Trends Biomater Artif Organs, 18, pp. 213-218; Lieberman, J., Daluiski, A., Einhorn, T., The role of growth factors in the repair of bone: biology and clinical applications (2002) J Bone Joint Surg, 84, pp. 1032-1044; Carson, J., Bostrom, M., Synthetic bone scaffolds and fracture repair (2007) Injury, 38, pp. S33-S70; Regí-Vallet, M., Balas, F., Colilla, M., Manzano, M., Drug confinement and delivery in ceramic implants (2007) Drug Metabol Lett, 1, pp. 37-40; Lin, T.-L., Lu, F.-M., Conroy, S., Sheu, M.-S., Su, S.-H., Tang, L., Antimicrobial coatings: a remedy for medical device-related infections (2001) Med Device Technol., 12, pp. 26-30; Beardmore, A., Brooks, D., Wenke, J., Thomas, D., Effectiveness of local antibiotic delivery with an osteoinductive and osteoconductive bone-graft substitute (2005) J Bone Joint Surg, 87, pp. 107-112; Gomes, P., Fernandes, M., Effect of therapeutic levels of doxycycline and minocycline in the proliferation and differentiation of human bone marrow osteoblastic cells (2007) Arch Oral Biol, 52, pp. 251-259; Coelho, M., Fernandes, M., Human bone cell cultures in biocompatibility testing Part II. Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Jørgensen, N., Henriksena, Z., Sørensena, O., Civitelli, R., Dexamethasone, BMP-2, and 1,25-dihydroxyvitamin D enhance a more differentiated osteoblast phenotype: validation of an in vitro model for human bone marrow-derived primary osteoblasts (2004) Steroids, 69, pp. 219-226; Sakellari, D., Goodson, J., Socransky, S., Kolokotronis, A., Konstantinidis, A., Concentration of 3 tetracyclines in plasma, gingival crevice fluid and saliva (2000) J Clin Periodontol, 27, pp. 53-60; Stein, G., Lian, J., Molecular mechanisms mediating proliferation/differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocr Rev, 14, pp. 424-442; Zhang, Y., Lopes, M., Santos, J., CaO-P 2O 5 Glass ceramics containing bioactive phases: crystallization and in vitro bioactivity studies (2001) Key Eng Mater, 192, pp. 643-646; Lopes, M., Knowles, J., Santos, J., Monteiro, F., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Costa, M., Gutierres, M., Almeida, L., Lopes, M., Santos, J., Fernandes, M., In vitro mineralisation of human bone marrow cells cultured on Bonelike (2004) Key Eng Mater, pp. 254-256. , (821-4); Lopes, M., Santos, J., Monteiro, F., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gutierres, M., Hussain, N., Lopes, M., Afonso, A., Cabral, A., Almeida, L., Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike ® synthetic bone graft (2006) J Ortho Res, 24, p. 953; Kima, H.-W., Leea, E.-J., Kima, H.-E., Salihb, V., Knowles, J., Effect of fluoridation of hydroxyapatite in hydroxyapatite-polycaprolactone composites on osteoblast activity (2005) Biomaterials, 26, pp. 4395-4404; Williams, S., Barnes, J., Wakisaka, A., Ogasa, H., Liang, C., Treatment of osteoporosis with MMP inhibitors (1999) Ann NY Acad Sci, 878, pp. 191-200; Schwartz, Z., Lohmann, C., Wieland, M., Cochran, D., Dean, D., Textor, M., Osteoblast proliferation and differentiation on dentin slices are modulated by pretreatment of the surface with tetracycline or osteoclasts (2000) J Periodontol, 71, pp. 586-597; Bettany, J., Wolowacz, R., Tetracycline derivatives induce apoptosis selectively in cultured monocytes and macrophages but not in mesenchymal cells (1998) Adv Dent Res, 12, pp. 136-143; Duewelhenke, N., Krut, O., Eysel, P., Influence on mythochondria and cytotoxicity of different antibiotics administered in high concentrations on primary human osteoblasts and cell lines (2007) Antimicrobial Agents and Chemotherapy, 51, pp. 54-63; Golub, L., Wolff, M., Roberts, S., Lee, H.-M., Leung, M., Payonk, G., Treating periodontal diseases by blocking tissue-destructive enzymes (1994) JADA, 125, pp. 163-169; Woessner, J., Nagase, H., Inhibition of MMPs (2000) MMPs and Timps, pp. 109-125. , Woessner J., and Nagase H. (Eds), Oxford University Press, Oxford; Golub, L., Ramamurthy, N., McNamara, T., Gomes, B., Wolff, M., Casino, A., Tetracyclines inhibit tissue collagenase activity. A new mechanism in the treatment of periodontal disease (1984) J Periodontal Res, 19, pp. 651-655; Yu, Z., Ramamurthy, N., Leung, M., Chang, K., McNamara, T., Golub, L., Chemically-modified tetracycline normalizes collagen metabolism in diabetic rats: a dose-response study (1993) J Periodontal Res, 28, pp. 420-428; Karimbux, N., Ramamurthy, N., Golub, L., Nishimura, I., The expression of collagen I and XII on RNAs in porphyromonas gingivalis-induced periodontitis in rats: The effect of doxycycline and chemically-modified tetracycline (CMT-1) (1998) J Periodontol, 69, pp. 39-40; Ramamurthy, N., Pirila, E., Lee, H.-M., Delayed wound healing, altered collagen level and keratinocyte growth factor expression in skin of ovariectomized rat is normalized by estrogen or chemically modified doxycycline (2003) Menopause - The State of the Art in Research and Management. The Proceedings of the Tenth World Congress, pp. 236-243. , Schneider H. (Ed), Parthenon Publishing Group, New York; Gurkan, A., Çunarcuk, S., Huseyinov, A., Adjunctive subantimicrobial dose doxycycline: effect on clinical parameters and gingival crevicular fluid transforming growth factor-b 1 levels in severe, generalized chronic periodontitis (2005) J Clin Periodontol, 32, pp. 244-253; Caton, J., Evaluation of Periostat for patient management (1999) Compend Contin Edu Dent, 20, pp. 451-456; Salasznyk, R., Williams, W., Boskey, A., Batorsky, A., Plopper, G., Adhesion to vitronectin and collagen I promotes osteogenic differentiation of human mesenchymal stem cells (2004) J Biomed Biotechnol, 1, pp. 24-34; Gerstenfeld, L., Chipman, S., Kelly, C., Hodgens, K., Lee, D., Landis, W., Collagen expression, ultrastructural assembly, and mineralization in cultures of chicken embryo osteoblasts (1988) J Cell Biol, 106, pp. 979-989
Keywords: adult; alkaline phosphatase; alkaline phosphatase bone isoenzyme; antimicrobial activity; article; Bacteria (microorganisms); bone infection; bone marrow cell; Bone Marrow Cells; Bone Substitutes; Bonelike; Calcium; calcium phosphate; Cell culture; cell function; cell proliferation; cell survival; cell viability; Cells, Cultured; concentration response; controlled study; Culture Media; culture medium; doxycycline; Durapatite; enzyme activity; extracellular matrix; glass; human; human cell; Humans; hydroxyapatite; implant; Microscopy, Electron, Scanning; Middle Aged; Minerals; minocycline; osteoblast; Osteoblasts; priority journal; Scanning electron microscopy; stroma cell; Tetracycline; tetracycline derivative; Tetracyclines; X-Ray Diffraction

Changes in detrended fluctuation indices with aging in healthy and congestive heart failure subjects - Barquero-Pérez, Ó.; De Sá, J.M.; Rojo-Álvarez, J.L.; Goya-Esteban, R. (Computers in CardiologyComput Cardiol, 2008)
Detrended Fluctuation Analysis (DFA) aims to quantify the fractal correlation properties in nonstationary time series, and it has successfully been applied in the assessment of the Heart Rate Variability (HRV) for cardiac risk stratification purposes. However the physiological meaning of DFA indices and its relation with aging have not yet been completely established. Given that a loss of complexity in the physiological regulation of elderly subjects has been reported in the literature, we hypothesized that DFA indices could be modified by aging. In this work we computed the Hurst exponent (estimated using DFA method) and DFA indices α 1 and α 2 to assess the HRV in healthy and Congestive Heart Failure (CHF) subjects, and we studied the dependence of these indices on aging for both healthy and CHF subjects. We found that only α2 and Hurst exponent, and only in the case of healthy subjects, have significant discrimination capability to distinguish between young and elderly groups, and also that these indices have a steady increase with aging. Therefore, we can conclude that the loss of complexity due to aging can be quantified by changes in the values of α 2 and Hurst exponent.
Conference code: 75561Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 4748973CODEN: COCADdoi: 10.1109/CIC.2008.4748973Language of Original Document: EnglishCorrespondence Address: Barquero-Pérez, Ó.; B-013, Universidad Rey Juan Carlos, Camino del Molino s/n, Fuenlabrada-28943 Madrid, Spain; email: obarquero@gmail.comReferences: Goldberger, A.L., Nonlinear dynamics, fractals, and chaos theory: Implications for neuroautonomic heart rate control in health and disease (1999) The Autonomic Nervous System, , Bolis C, Licinnio J eds, Geneva: World Health Organization;Peng, C.K., Havlin, S., Stanley, H.E., Goldberger, A.L., Quantification of scaling exponents and crossover phenomena in nonstationary heartbeat time series (1995) Chaos, 5, pp. 82-87; Goldberger, A.L., Amaral, L.A.N., Hausdorff, J.M., Ivanov, P.C., Peng, C.K., Stanley, H.E., Fractal dynamics in physiology: Alterations with disease and aging (2002) Proceedings of the National Academy of Sciences, 99, p. 119; Berger, R.D., Broken fractals: Where's the break? (2001) Journal of Cardiovascular Electrophysiology, 12 (1), pp. 33-35; Mandelbrot, B.B., van Ness, J.W., Fractional Brownian motions, fractional noises and applications (1968) SIAM Review, 10, pp. 422-437; Kantelhardt, J.W., Zschiegner, S.A., Koscielny-Bunde, E., Havlin, S., Bunde, A., Stanley, H.E., Multifractal detrended fluctuations analysis of nonstationary time series (2002) Physica A, 316, pp. 87-114; Goldberger, A.L., Amaral, L.A.N., Glass, L., Hausdorff, J.M., Ivanov, P.C., Mark, R.G., Mietus, J.E., Stanley, H.E., PhysioBank, PhysioToolkit, and PhysioNet: Components of a new research resource for complex physiologic signals (2000) Circulation, 101 (23), pp. e215-e220. , June 13; Malik, M., Cripps, T., Farrell, T., Camm, A., Prognostic value of heart rate variability after myocardial infarction. a comparison of different data-processing methods (1989) Medical and Biological Engineering and Computing, 27, pp. 603-621; Huikuri, H.V., Mäkikallio, T.H., Perkiömäki, J., Measurement of heart rate variability by methods based on nonlinear dynamics (2003) Journal of Electrocardiology, 36, pp. 95-99; Rojo-Álvarez, J., Sánchez-Sánchez, A., Barquero-Prez, O., Goya-Esteban, R., Everss, E., Mora-Jímenez, I., García-Alberola, A., Analysis of physiological meaning of detrended fluctuation analysis in heart rate variability using a lumped parameter model (2007) Computers in Cardiology, 34, pp. 25-28
Keywords: Cardiology; Congestive heart failures; Correlation properties; Detrended fluctuation analysis; DFA methods; Healthy subjects; Heart rate variabilities; Heart valve prostheses; Hurst exponents; Non-stationary time series; Risk analysis; Risk perception; Risk stratifications; Table lookup; Time series; Time series analysis

Characterization of heart rate variability loss with aging and heart failure using sample entropy - Goya-Esteban, R.; De Sá, J.P.M.; Rojo-Álvarez, J.L.; Barquero-Pérez, O. (Computers in CardiologyComput Cardiol, 2008)
Entropy based measures, such as Sample Entropy (SampEn), have been widely used for quantifying the Heart Rate Variability (HRV) for cardiac risk stratification purposes, with the hypothesis that decreasing entropy points to a perturbation of the complex physiological mechanisms or disease. However, in the literature, higher entropy values have been reported for some pathologies than for healthy subjects, which could be due to the use of a threshold value r tuned relative to the signal standard deviation. In the present paper we apply SampEn to assess the variability of the RR time series from healthy subjects and subjects with Congestive Heart Failure (CHF) in order to discriminate between both groups, as well as to characterize the variability loss due to aging. We conclude that the use of a fixed threshold value r in the SampEn algorithm instead of its conventional setting (as a percentage of the standard deviation of each data series), improves the discrimination capabilities between healthy and CHF subjects, and it allows to quantify the loss of HRV due to aging in healthy subjects.
Conference code: 75561Export Date: 21 November 2012Source: ScopusArt. No.: 4748972CODEN: COCADdoi: 10.1109/CIC.2008.4748972Language of Original Document: EnglishCorrespondence Address: Goya-Esteban, R.; Universidad Rey Juan Carlos, Camino del Molino s/n, Fuenlabrada-28943 Madrid, Spain; email: rebegoya@gmail.comReferences: Pincus, S.M., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci, 88, pp. 2297-2301;Pincus, S.M., Goldberger, A.L., Physiological time-series analysis: What does regularity quantify? (1994) Am J Physiol Heart Circ Physiol, 35, pp. 1643-1656; Pincus, S.M., Assesing serial irregularity and its implications for health (2001) Annals New York Academy of Sciences, 954, pp. 245-267; Marques-de, S.J., Characterization of fetal heart rate using approximate entropy (2005) IEEE Computers in Cardiology, 32, pp. 671-673; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. 2039-2049; Goldberger, A.L., Amaral, L.A.N., Glass, L., Hausdorff, J.M., Ivanov, P.C., Mark, R.G., Mietus, J.E., Stanley, H.E., PhysioBank, PhysioToolkit, and PhysioNet: Components of a new research resource for complex physiologic signals (2000) Circulation, 101 (23), pp. e215-e220. , June 13; Malik, M., Cripps, T., Farrell, T., Camm, A., Prognostic value of heart rate variability after myocardial infarction. a comparison of different data-processing methods (1989) Medical and Biological Engineering and Computing, 27, pp. 603-621; Signorini, M., Ferrario, M., Marchetti, M., Marseglia, A., Nonlinear analysis of heart rate variability signal for the characterization of cardiac heart failure patients (2006) Conf Proc IEEE Eng Med Biol Soc, 1 (1), pp. 3431-3434
Keywords: Cardiology; Congestive heart failures; Data series; entropy; Entropy values; Fixed thresholds; Healthy subjects; Heart failures; Heart rate variabilities; Heart valve prostheses; Physiological mechanisms; Risk stratifications; Sample entropies; Signal standard deviations; Standard deviations; Table lookup; Time series

Chromatographic pattern classification - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (IEEE Transactions on Biomedical EngineeringIEEE Trans. Biomed. Eng., 2008)
In this paper, we propose and evaluate methodologies for the classification of images from thin-layer chromatography. Each individual sample is characterized by an intensity profile that is further represented into a feature space. The first steps of this process aim at obtaining a robust estimate of the intensity profile by filtering noise, reducing the influence of background changes, and by fitting a mixture of Gaussians. The resulting profiles are represented by a set of appropriate features trying to characterize the state of nature, here spread out over four classes, one for normal subjects and the other three corresponding to lysosomal diseases, which are disorders responsible for severe nerve degeneration. For classification purposes, a novel solution based on a hierarchical structure is proposed. The main conclusion of this paper is that an automatically generated decision tree presents better results than more conventional solutions, being able to deal with the natural imbalance of the data that, as consequence of the rarity of lysosomal disorders, has very few representative cases in the disease classes when compared with the normal population. © 2008 IEEE.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusArt. No.: 8CODEN: IEBEAdoi: 10.1109/TBME.2008.919852PubMed ID: 18714832Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica (INEB), Instituto Superior de Engenharia Do Porto, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptChemicals/CAS: Hydrolases, EC 3.-References: Keir, G., Winchester, B., Clayton, P., Carbohydrate-deficient glycoprotein syndromes: Inborn errors of protein glycosylation (1999) Ann. Clin. Biochem, 36 (1), pp. 20-36;Durand, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clin. Chem, 46, pp. 795-805; Scriver, S., Beaudet, A., Sly, W., Valle, D., (2001) The Metabolic Bases of Inherited Disease, 3. , New-York: McGraw-Hill; Pinto, R., Caseiro, C., Lemos, M., Lopes, L., Fontes, A., Miranda, M., Prevalence of lysosomal storage diseases in Portugal (2004) Eur. J. Hum. Genet, 12, pp. 87-92; Friedman, R., Williams, M., Moser, H., Kolodny, E., Improved thin-layer chromatographic method in the diagnosis of mannosidosis (1978) Clin. Chem, 24, pp. 1576-1577; Kurczynski, T., Kendzierski, K., Sewell, A., Kuczynski, T., Urinary oligosaccharides in pregnant or lactating women: Pitfall in screening (1993) Clin. Chem, 39, pp. 2346-2347; Sewell, A., Urinary oligosaccharides (1991) Techniques Diagnostic Human Biochemical Genetics, pp. 219-231. , New York: Wiley; Reich, E., Blatter, A., Modern TLC: A key technique for identification and quality control of botanicals and dietary supplements (2005) J. Planar Chromatogr. - Modern TLC, 18, pp. 34-37. , Jan./Feb; Duvdevani-Bar, S., Edelman, S., Visual recognition and categorization on the basis of similarities to multiple class prototypes (1999) Int. J. Comput. Vis, 33, pp. 201-228; Pekalska, E., Duin, R., Dissimilarity representations allow for building good classifiers (2002) Pattern Recognit. Lett, 23, pp. 943-956; Goldstone, R., Son, J., Similarity (2005) Cambridge Handbook of Thinking and Reasoning, pp. 13-36. , K. Holyoak and R. Morrison, Eds. Cambridge, MA: Cambridge Univ. Press; Lavine, B., Clustering and classification of analytical data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , R. Meyers, Ed. Chichester, U.K, Wiley; Japkowicz, N., Learning from imbalanced data sets: A comparison of various strategies (2000) Proc. Learn. Imbalanced Data, pp. 10-15; Weiss, G., Mining with rarity: A unifying framework (2004) Sigkdd Explor, 6, pp. 7-19; Kubat, M., Holte, R., Matwin, S., Machine learning for the detection of oil spills in satellite radar images (1998) Mach. Learn, 30, pp. 195-215; Tax, D., One-class classification; concept-learning in the absence of counter-examples, (2001), ASCI, pp. 1-190. , Ph.D. dissertation, Delft Univ. Technol, Dissertation Ser, ppSousa, A., Aguiar, R., Mendonça, A., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) Lecture Notes in Computer Science, 3212, pp. 158-165. , Image Analysis and Recognition, New York: Springer-Verlag; Schwedt, G., (1997) The Essential Guide to Analytical Chemistry, , New York: Wiley; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput. Methods Programs Biomed, 77, pp. 209-231; Eibrand, R., Kennedy, P., Cotter, D., MacEvilly, U., Wu, B., Analysis of Atlantic salmon skin mucus: COPS - A computer-based system for protein pattern analysis of 1D SDS-PAGE gels (2003) Proc. IEEE Symp. Bioinf. BioEng, pp. 45-52; Gerasimov, A., Use of the software processing of scanned chromatogram images in quantitative planar chromatography (2004) J. Anal. Chem, 59, pp. 348-353; Goulding, P., (2000) Electrophoresis Gel Analysis Software: Important Aspects, p. 14. , Cambridge, U.K, UVItec Ltd; Jedra, M., El Khattabi, N., Limouri, M., Essaid, A., Recognition of seed varieties using a time-delay neural network: Analysis of electrophoretic images (1999) Comput. Electron. Agric, 22, pp. 1-10; Machado, A., Campos, M., Siqueira, A., Carvalho, O., An iterative algorithm for segmenting lanes in gel electrophoresis images (1997) Proc. Comput. Graph. Image Process. X Braz. Symp, pp. 140-146. , Campos do Jordao, Brazil, Oct; Ye, X., Suen, C., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Proc. Vis. Interface, pp. 432-438; Shadle, S., Allen, D., Guo, H., Pogozelski, W., Bashkin, J., Tullius, T., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of a protein-DNA binding constant (1997) Nucleic Acids Res, 25, pp. 850-860; Bajla, I., Hollander, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) Meas. Sci. Rev, 1, pp. 5-10; Bajla, I., Hollander, I., Burg, K., Fluch, S., A novel approach to quantitative analysis of electrophoretic gel images of DNA fragments (2002) Proc. IEEE Int. Symp. Biomed. Imag, pp. 899-902; Lonni, A., Scarminio, I., Silva, L., Ferreira, D., Differentiation of species of Baccharis Genus by HPLC and chemometrics methods (2003) Anal. Sci, 19, pp. 1013-1017; Beltrán, N., Duarte-Mermoud, M., Salah, S., Bustos, M., Feature selection algorithms using Chilean wine chromatograms as examples (2005) J. Food Eng, 67, pp. 483-490; Landgrebe, D., Information extraction principles and methods for multispectral and hyperspectral image data (2000) Information Processing for Remote Sensing, , Hackensack, NJ: World Scientific, ch. 1; Landgrebe, D., Hyperspectral image data analysis as a high dimensional signal processing problem (2002) IEEE Signal Process. Mag, 19 (1), pp. 17-28. , Jan; Jimenez, L., Landgrebe, D., Hyperspectral data analysis and feature reduction via projection pursuit (1999) IEEE Trans. Geosci. Remote Sens, 37 (6), pp. 2653-2667. , Nov; Jimenez, L., Landgrebe, D., Supervised classification in high- dimensional space: Geometrical, statistical, and asymptotical properties of multivariate data (1998) IEEE Trans. Syst., Man, Cybern, 28 (1), pp. 39-54. , Pt. C, Feb; Marques deSá, J., (2001) Pattern Recognition - Concepts, Methods and Applications, , Berlin, Germany: Springer-Verlag; Heijden, F., Duin, R., Ridder, D., Tax, D., (2004) Classification, Parameter Estimation and State Estimation, , New York: Wiley; Dudoit, S., Fridlyand, J., Speed, T., Comparison of discrimination methods for the classification of tumors using gene expression data (2002) J. Amer. Stat. Assoc, 97, pp. 77-87; Zomer, S., Brereton, R., Carter, J., Eckers, C., Support vector machines for the discrimination of analytical chemical data: Application to the determination of tablet production by pyrolysis-gas chromatography-mass spectrometry (2004) Analyst, 129, pp. 175-181; Zomer, S., Guillo, C., Brereton, R., Hanna-Brown, M., Toxicological classification of urine samples using pattern recognition techniques and capilarity electrophoresis (2003) Anal. Bioanal. Chem, 378, pp. 2008-2020; Fan, X., Bai, J., Shen, P., Diagnosis of breast cancer using HPLC metabonomics fingerprints coupled with computational methods (2005) 27th Annu. Conf. Eng. Med. Biol, pp. 6081-6084. , Shanghai, China; Skurichina, M., Raudys, S., Duin, R., K-nearest neighbors directed noise injection in multilayer perceptron training (2000) IEEE Trans. Neural Netw, 11 (2), pp. 504-511. , Mar; Ha, T., Bunke, H., Off-line, handwritten numeral recognition by perturbation method (1997) IEEE Trans. Pattern Anal. Mach. Intell, 19, pp. 535-539; Lee, S., Noisy replication in skewed binary classification (2000) Comput. Stat. Data Anal, 34, pp. 165-191; Demant, C., Streicher-Abel, B., Waszkewitz, P., (1999) Industrial Image Processing, , New York: Springer-Verlag; Dempster, A., Laird, N., Rubin, D., Maximum likelihood from incomplete data via the EM algorithm (1977) J. Roy. Stat. Soc. B, 39 (1), pp. 1-38; Moré, J., Sorensen, D., Computing a trust region step (1983) SIAM J. Sci. Stat. Comput, 4, pp. 553-572; Byrd, R., Schnabel, R., Shultz, G., Approximate solution of the trust region problem by minimization over two-dimensional subspaces (1988) Math. Program, 40, pp. 247-263; Sousa, A., Mendonça, A., Campilho, A., Aguiar, R., Miranda, C., Feature extraction for classification of thin-layer chromatography images (2005) Lecture Notes in Computer Science, 3656, pp. 974-981. , Image Analysis and Recognition, New York: Springer-Verlag; Ripley, B., (2004) Pattern Recognition and Neural Networks, , New York: Cambridge Univ. Press; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) ICML 2003, Workshop Learn. Imbalanced Datasets, 2. , presented at the, Washington, DC
Keywords: Acoustic variables control; Algorithms; article; Chromatographic analysis; Chromatographic pattern features; Chromatographic profiles; Chromatography; Chromatography, Thin Layer; Classification; Diagnosis, Computer-Assisted; Gaussian noise (electronic); Hierarchical classifier; Humans; Hydrolases; imaging; Lysosomal Storage Diseases; lysosome storage disease; mathematical analysis; nerve degeneration; noise; normal distribution; Pattern recognition; Pattern Recognition, Automated; Reproducibility of Results; sensitivity and specificity; Urinalysis

A clinical report of bone regeneration in maxillofacial surgery using bonelike® synthetic bone graft - Sousa, R.C.; Lobato, J.V.; Maurício, A.C.; Hussain, N.S.; Botelho, C.M.; Lopes, M.A.; Santos, J.D. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2008)
The objective of this study is to evaluate the osteoconductivity and bioactivity of the Bonelike® graft in repairing surgical cystic bone defects. Bonelike® is implanted in 11 patients, aged between 24 and 53 years with a mean age of 36 years, consisting of 5 men and 6 women. According to the standard follow up protocols, radiological examinations are performed and Bonelike® /bone retrieved samples have been analyzed histologically using non-decalcified sections obtained perpendicular to bone length axis. Radiographic examination and histological results clearly demonstrate an extensive new bone formation apposed on Bonelike® granules with a significant degree of maturation. These clinical applications in maxillary bone defects indicate perfect bone bonding between new bone formed and Bonelike® granules, along with partial surface biodegradation. This quick and effective osteoconductive response from Bonelike® may reduce the time needed to reconstruct the bone defected area of patients. © 2008 Sage Publications.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JBAPEdoi: 10.1177/0885328207078260Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesReferences: Mohamed, A., Sudha, K., Kim, F., Karl, K., Scott, P.B., Bone Graft Substitutes (2003) Cell Based Approaches for Bone Graft Substitutes, p. 127. , In: Laurencin, C.T. (ed.), Chapter 7 ASTM - International, USA;Mellonig, J.T., Prewett, A.B., Moyer, M.P., HIV Inactivation in a Bone Allograft (1992) J. Periodontol., 63, p. 979; Buck, B.E., Malinin, T.I., Brown, M.D., Bone Transplantation and Human Immunodeficiency Virus. An Estimate of Risk of Acquired Immunodeficiency Syndrome (AIDS) (1989) Clin. Orthop., 240, p. 129; Mary, E.A.R., Raymond, A.Y., Bone Replacement Grafts - The Bone Substitutes (1998) Dent. Clin. North Am., 42 (3), p. 491; Doron, I.I., Amy, L.L., Bone Graft Substitutes (2002) Oper. Tech. Plast. Reconsr. Surg., 9 (4), p. 151; Wright, S., Commentary The Bone-Graft Market in Europe, in Emerging Technologies in Orthopedics I: Bone Graft Substitutes (1999) Bone Growth Stimulators and Bone Growth Factors By Datamonitor Plc, p. 591; Knaack, D., Goad, M.E.P., Aiolova, M., Christian, R., Ali, T., Promod, C., Duke Lee, D., Resorbable Calcium Phosphate Bone Substitute (1998) J. Biomed. Mater. Res., 43, p. 399; Frayssinet, P., Trouillet, J.L., Rouquet, N., Azimus, E., Autefage, A., Osseointegration Macroporous Calcium Phosphate Ceramics Having a Different Chemical Composition (1993) Biomaterials, 14, p. 423; Klein, C.P.A.T., Driessen, A.A., Groot de, K., van den Hooff, A., Biodegradation Behavior of Various Calcium Phosphate Materials in Bone Tissue (1983) J. Biomed. Mater. Res., 17, p. 769; Daculsi, G., Biphasic Calcium Phosphate Concept Applied to Artificial Bone, Implant Coating and Injectable Bone Substitute (1998) Biomaterials, 19, p. 1473; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof (1999) Worldwide Applications, , (PCT), Patent No. 1 189 851; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass Reinforced Hydroxyapatite: A Comprehensive Study of the Effect of Glass Composition on the Crystallography of the Composite (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced Hydroxyapatite Composites: Fracture Toughness and Hardness Dependence on Microstructural Characteristics (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., Microstructural Dependence of Young's and Shear Moduli of P 2 O 2 Glass Reinforced Hydroxyapatite for Biomedical Applications (2000) Biomaterials, 21, p. 749; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out Testing and Histological Evaluation of Glass Reinforced Hydroxyapatite Composites Implanted in the Tibia of Rabbits (2001) J. Biomed. Mater. Res., 54, p. 463; Lobato, J.V., Hussain, N.S., Botelho, C.M., Rodrigues, J.M., Luís, A.L., Maurício, A.C., Lopes, M.A., Santos, J.D., Assessment of the Potential of Bonelike® Graft for Bone Regeneration by using an Animal Model (2005) Key. Eng. Mater., 877, pp. 284-286; Lobato, J.V., Hussain, N.S., Botelho, C.M., Mauricio, A.C., Afonso, A., Ali, N., Santos, J.D., Assessment of Bonelike® Graft with a Resorbable Matrix using an Animal Model (2006) Thin Solid Films, 515, p. 362; Duarte, F., Santos, J.D., Afonso, A., Medical Applications of Bonelike® in Maxillofacial Surgery (2004) Mater. Sci. Forum, 370, pp. 455-456; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., Biological Behaviour of Bonelike® Graft Implanted in Tibia of Humans (2005) Key Eng. Mater., 1041, pp. 284-286; LeGeros, R.Z., Properties of Osteoconductive Biomaterials: Calcium Phosphates (2002) Clin. Orthop., 395, p. 81; Robert, D.A.G., Hanneke, G.T., Ronald, J.H., Buma, P., Mechanism of Bone Incorporation of β-TCP Bone Substitute in Open Wedge Tibial Osteotomy in Patients (2005) Biomaterials, 26, p. 6713; Hirotsugu, H., Norio, A., Kimimitsu, O., Noritaka, F., Ohnishi, H., Okada, A., Nomura, S., Maeda, T., A Histological Evaluation on Self setting α-tricalcium Phosphate Applied in the Rat Bone Cavity (2004) Biomaterials, 25, p. 431; Meinel, L., Betz, O., Fajardo, R., Hofmann, S., Nazarian, A., Cory, E., Hilbe, M., Kirker-Head, C., Silk Based Biomaterials to Heal Critical Sized Femur Defects (2006) Bone, 39, p. 922; Lim, S.C., Lee, M.J., Yeo, H.H., Effects of Various Implant Materials on Regeneration of Calvarial Defects in Rats (2000) Pathol. Int., 50, p. 594; Carano, R.A.D., Filvaroff, E.H., Angiogenesis and Bone Repair (2003) Drug Discov. Today, 21, p. 980; Gutierres, M., Hussain, N.S., Lopes, M.A., Afonso, A., Cabral, A.T., Almeida, L., Santos, J.D., Histomorphometric Measurements Histological and SEM Analyses of bone/ implant Interface: Clinical Trials using Bonelike® Granules (2006) J. Orthop. Res., 24, p. 953
Keywords: adult; article; Bioactivity; Bone; bone prosthesis; Bone Regeneration; Bone Substitutes; bone transplantation; Bonelike®; clinical trial; facial bone; Facial Bones; Female; Histological studies; histology; human; Humans; Implants (surgical); instrumentation; male; Maxillofacial surgery; methodology; Middle Aged; oral surgery; Pathology; Radiography; Radiology; Regeneration; Surgery; Surgery, Oral; Synthetic bone graft; treatment outcome

Comparative study of nanohydroxyapatite microspheres for medical applications - Mateus, A.Y.P.; Barrias, C.C.; Ribeiro, C.; Ferraz, M.P.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
This study concerns the preparation, physical, and in vitro characterization of two different types of hydroxyapatite (HA) microspheres, which are intended to be used as drug-delivery systems and bone-regeneration matrices. Hydroxyapatite nanoparticles (HA-1 and HA-2) were prepared using the chemical precipitation synthesis with H 3PO 4, Ca(OH) 2, and a surfactant, SDS (sodium dodecyl sulfate), as starting reagents. The HA powders were dispersed in a sodium alginate solution, and spherical particles were obtained by droplet extrusion coupled with ionotropic gelation in the presence of Ca 2+. These were subsequently sintered to produce HA-1 and HA-2 microspheres with a uniform size and interconnected microporosity. Both powders and microspheres were characterized using FTIR and X-ray diffraction. Moreover, SEM and mercury intrusion porosimetry were used to analyze the microspheres, and TEM was used to analyze the powders. Results showed that pure HA and mixtures of HA/β-TCP in the nanometer range and needlelike shape were obtained for HA-1 and HA-2 powders, respectively. Neutral Red, scanning electron microscopy and confocal microscopy were used to evaluate the behavior of osteoblastic-like MG-63 cells cultured on HA microspheres surfaces for 7 days. Results showed that good adhesion and proliferation of osteoblasts on the HA microspheres surface. Cells built bridges between adjacent microspheres, forming microspheres-cells clusters in both types of materials. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31634PubMed ID: 17975824Language of Original Document: EnglishCorrespondence Address: Mateus, A. Y. P.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: yovana@ibmc.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; calcium hydroxide, 1305-62-0; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; calcium, 7440-70-2; dodecyl sulfate sodium, 151-21-3; neutral red, 553-24-2; phosphoric acid, 7664-38-2; Biocompatible Materials; Durapatite, 1306-06-5; PowdersReferences: Jarcho, M., Calcium phosphates ceramics as hard tissue prosthetics (1981) Clin Orthop Relat Res, 157, pp. 259-278;Bucholz, R., Carlton, A., Holmes, R., Hydroxyapatite and tricalcium phosphate bone graft substitutes (1987) Orthop Clin N Am, 18, pp. 323-334; Daculsi, G., Passuti, N., Martins, S., Deudon, C., LeGeros, R., Raher, S., Macroporous calcium phosphate ceramic for ling bone surgery in humans and dogs: Clinical and histological study (1990) J Biomed Mater Res, 24, pp. 379-396; Gauthier, O., Bouler, J., Weiss, P., Bosco, J., Daculsi, G., Aguado, E., Kinetic study of bone in growth and ceramic resorption associated with the implantation of different injectable calcium-phosphate bone substitutes (1999) J Biomed Mater Res, 47, pp. 28-35; Rey, C., Calcium phosphate biomaterials and bone mineral: Differences in composition, structures and properties (1990) Biomaterials, 11, pp. 13-15; Yuan, H., Kurashina, K., de Bruijn, J., Li, Y., de Groot, K., Zhang, X., A preliminary study on osteoinduction of two kinds of calcium phosphate ceramics (1999) Biomaterials, 20, pp. 1799-1806; Liou, S., Chen, S., Liu, D., Synthesis and characterization of needlelike apatitic nanocomposite with controlled aspect ratios (2003) Biomaterials, 24, pp. 3981-3988; Earl, J.S., Wood, D.J., Mile, S.J., Hydrothermal synthesis of hydroxyapatite (2006) J Phys Conf, 26, pp. 268-271; Han, J.K., Song, H.Y., Fumio, S., Lee, B.T., Synthesis of high purity nano-sized hydroxyapatite powder by microwave-hydrothermal method (2006) Mater Chem Phys, 99, pp. 235-239; Yoshimura, M., Sujaridworakun, P., Koh, F., Fujiwara, T., Pongkao, D., Ahniyaz, A., Hydrothermal conversion of calcite crystals to hydroxyapatite (2004) Mater Sci Eng C, 24, pp. 521-525; Bogdanoviciene, I., Beganskiene, A., Tonsuaadu, K., Glaser, J., Meyer, H.J., Kareiva, A., Calcium hydroxyapatite Ca 10(PO 4) 6 (OH) 2 ceramics prepared by aqueous sol-gel processing (2006) Mater Res Bull, 41, pp. 1754-1762; Liu, D.M., Troczynski, T., Tseng, W.J., Water-based sol-gel synthesis of hydroxyapatite: Process development (2001) Biomaterials, 22, pp. 1721-1730; Bezzi, G., Celotti, G., Landi, E., La Torretta, T.M.G., Sopyan, I., Tampieri, A., A novel sol-gel technique for hydroxyapatite preparation (2003) Mater Chem Phys, 78, pp. 816-824; An, G.H., Wang, H.J., Kim, B.H., Jeong, Y.G., Choa, Y.H., Fabrication and characterization of a hydroxyapatite nanopowder by ultrasonic spray pyrolysis with salt-assisted decomposition (2007) Mater Sci Eng A, pp. 449-451,821-824; Varma, H.K., Babu, S., Synthesis of calcium phosphate bioceramics by citrate gel pyrolisis method (2005) Ceram Int, 31, pp. 109-114; Jarudilokkula, S., Tanthapanichakoonb, W., Boonamnuayvittayaa, V., Synthesis of hydroxyapatite nanoparticles using an emulsion liquid membrane system Colloids Surf A, , Forthcoming; Bose, S., Saha, S.K., Synthesis and characterization of hydroxyapatite nanopowders by emulsion technique (2003) Chem Mater, 15, pp. 4464-4469; Nayar, S., Sihna, M.K., Basu, D., Sinha, A., Synthesis and sintering of biomimetic hydroxyapatite nanoparticles for biomedical applications (2006) J Mater Sci: Mater Med, 17, pp. 1063-1068; Tas, A.C., Synthesis of biomimetic Ca-hydroxyapatite powders at 37°C in synthetic body fluids (2000) Biomaterials, 21, pp. 1429-1438; Wanga, A., Yina, H., Liua, D., Wub, H., Wadac, Y., Rena, M., Xua, Y., Chenga, X., Effects of organic modifiers on the size-controlled synthesis of hydroxyapatite nanorods (2007) Appl Surf Sci, 253, pp. 3311-3316; Zhang, H.G., Zhu, Q., Surfactant-assisted preparation of fluoride-substituted hydroxyapatite nanorods (2005) Mater Lett, 59, pp. 3054-3058; Liu, Y., Houa, D., Wangb, G., A simple wet chemical synthesis and characterization of hydroxyapatite nanorods (2004) Mater Chem Phys, 86, pp. 69-73; Pang, Y.X., Bao, X., Influence of temperature, ripening time and calcination on the morphology and crystallinity of hydroxyapatite nanoparticles (2003) J Eur Ceram Soc, 23, pp. 1697-1704; Gitzhofer, B.E., Boulos, M.I., Morpholgical study of hydroxyapatite nanocrystal suspension (2000) J Mater Sci: Mater Med, 11, pp. 523-531; Barbosa, M., Granja, P., Barrias, C., Amaral, I., Polysaccharides as scaffolds for bone regeneration (2005) ITBM-RBM, 26, pp. 212-217; Hari, P., Chandy, T., Sharma, C., Chitosan/calcium-alginate beads for oral delivery of insulin (1996) J Appl Polym Sci, 59, pp. 1796-1801; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Key Eng Mater, pp. 254-262,877-880; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Preparation and characterisation of calcium-phosphate porous microspheres with a uniform size for biomedical applications (2006) J Mater Sci: Mater Med, 17, pp. 455-463; Bowersock, T., Martins, S., Vaccine delivery to animals (1999) Adv Drug Deliv Rev, 32, pp. 167-194; Kong, H., Smith, M., Mooney, D., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24, pp. 4023-4029; Legallais, C., David, B., Doré, E., Bioartificial livers (BAL): Current technological aspects and future developments (2001) J Membr Sci, 181, pp. 81-95; Liu, X.D., Yu, W.Y., Zhang, Y., Xue, W.M., Yu, W.T., Xiong, Y., Ma, X.J., Yuan, Q., Characterization of structure and diffusion behaviour of Ca-alginate beads prepared with external or internal calcium sources (2002) J Microencapsul, 19 (6 -1), pp. 775-782; Taqieddin, E., Amiji, M., Enzyme immobilization in novel alginate-chitosan coreshell microcapsules (2004) Biomaterials, 25, pp. 1937-1945; Ribeiro, C., Barrias, C., Barbosa, M., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373; Kim, Y.J., Park, H.G., Yang, Y.L., Yoon, Y., Kim, S., Oh, E., Multifunctional drug delivery system using starch-alginate beads for controlled release (2005) Biol Pharm Bull, 28, pp. 394-397; Barrias, C., Ribeiro, C., Lamghari, M., Sa, C., Barbosa, M., Proliferation, activity and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) J Biomed Mater Res A, 72, pp. 57-66; Mateus, A.Y.P., Ferraz, M.P., Monteiro, F.J., Microspheres based on hydroxyapatite nanoparticles aggregates for bone regeneration (2007) Key Eng Mater, pp. 330-332,243-246; Mankani, M., Fowler, B., Kingman, A., Robey, P., In vivo bone formation by human bone marrow stromal cells: Effect of carrier particle size and shape (2001) Biotechonol Bioeng, 72, pp. 96-107; Higashi, T., Okamoto, H., Influence of particle size of calcium phosphate ceramics as a capping agent on the formation of a hard tissue barrier in amputated dental pulp (1996) J Endodoncy, 22, pp. 281-283; Guo, G., Xun, Y., Wnag, Z., Guo, H., Preparation of hydroxyapatite nanoparticles by reverse microemulsion (2005) Ceram Int, 331, pp. 869-872; Sun, X.M., Chen, X., Deng, Z.X., Li, Y.D., A CTAB-assited hydrothermal orientation growth of ZnO nanorods (2002) Mater Chem Phys, 78, pp. 99-104; Uota, M., Arakawa, H., Kitamura, N., Yoshimura, T., Tanaka, J., Kijima, T., Synthesis of high surface area hydroxyapatite nanoparticles by mixed surfactant-mediated approach (2005) Langmuir, 21, pp. 4724-4728; Balasundaram, G., Sato, M., Webster, T.J., Using hydroxyapatite nanoparticles and decreased crystallinity to promote osteoblast adhesion similar to functionalizing with RGD (2006) Biomaterials, 27, pp. 2798-2805; Wutticharoenmongkol, P., Sanchavanakit, N., Pavasant, P., Supaphol, P., Novel bone scaffolds or electrospun polycaprolactone fibers filled with nanoparticles (2006) J Nanosci Nanotechnol, 6, pp. 514-522; Gonzalez-McQuire, R., Green, D., Walsh, D., Hall, S., Chane-Ching, J., Oreffo, R.O.C., Mann, S., Fabrication of hydroxyapatite sponges by dextran sulphate/amino acid templating (2005) Biomaterials, 26, pp. 6652-6656; Sun, W.B., Wu, Y.F., Ding, Y., Chu, C.L., Liu, T.J., The expression and activity of alkaline phosphatase in human periodontal ligament cells with nanometer hydroxyapatite (2006) Zhonghua Kou Qiang Yi Xue Za Zhi, 41, pp. 348-349; Bowers, K., Keller, J.C., Randolph, B., Wick, D., Michaels, C., Optimization of surface micromorphology for enhanced osteoblast responses in vitro (1992) Int J Oral Maxillofac Impl, 7, pp. 302-310; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford Jr, J., Dean, D.D., Boyan, B.D., Effect of titanium surface roughness on proliferation, differentiation, and protein synthesis of human osteoblast-like cells (MG63) (1995) J Biomed Mater Res, 29, pp. 389-401; Boyan, B.D., Batzer, R., Kieswetter, K., Liu, Y., Cochran, D.L., Szmuckler-Monclers, S., Dean, D.D., Schwartz, Z., Titanium surface roughness alters responsiveness of MG63 osteoblastic-like cells to 1α,25-(OH) 2D 3 (1998) J Biomed Mater Res, 39, pp. 77-85
Keywords: alginic acid; analytic method; Apatite; article; Biocompatible Materials; Biological materials; biomaterial; Bone Regeneration; Calcium; calcium hydroxide; calcium phosphate; cell adhesion; Cell Line; cell proliferation; Chemical precipitation; Chemotherapy; Comparative studies; comparative study; controlled study; dodecyl sulfate sodium; Drug delivery; Drug delivery system (DDS); Drug Delivery Systems; Drug dosage; Durapatite; Gelation; human; human cell; Humans; hydroxyapatite; Hydroxyapatite (HAP); Hydroxylation; In vitro characterization; in vitro study; infrared spectroscopy; materials testing; Medical applications; Mercury intrusion porosimetry; microsphere; Microspheres; Nano-hydroxyapatite (n-HA); Nanohydroxyapatite; nanoparticle; nanoparticles; neutral red; osteoblast; Osteoblasts; Particle Size; phosphoric acid; porosity; powder; Powders; precipitation; Precipitation (chemical); reagent; Regeneration (renovating); Scanning electron microscopy; surfactant; synthesis; Synthesis (chemical); X ray diffraction

Data classification with multilayer perceptrons using a generalized error function - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Neural NetworksNeural Netw., 2008)
The learning process of a multilayer perceptron requires the optimization of an error function E (y, t) comparing the predicted output, y, and the observed target, t. We review some usual error functions, analyze their mathematical properties for data classification purposes, and introduce a new one, E Exp, inspired by the Z-EDM algorithm that we have recently proposed. An important property of E Exp is its ability to emulate the behavior of other error functions by the sole adjustment of a real-valued parameter. In other words, E Exp is a sort of generalized error function embodying complementary features of other functions. The experimental results show that the flexibility of the new, generalized, error function allows one to obtain the best results achievable with the other functions with a performance improvement in some cases. © 2008 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: NNETEdoi: 10.1016/j.neunet.2008.04.004PubMed ID: 18572384Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; INEB-Instituto de Engenharia Biomédica, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Baum, E.B., Wilczek, F., Supervised learning of probability distributions by neural networks (1987) NIPS, pp. 52-61. , Anderson D.Z. (Ed), American Institute of Physics;Bishop, C., (1995) Neural networks for pattern recognition, , Oxford University Press; Blake, C., & Merz, C. (1998). UCI repository of machine learning databases. University of California, Irvine, Dept. of Information and Computer SciencesForina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of italian olive oils (1981) Annali di Chimica (Rome), 50, pp. 127-155; Gish, H. (1990). A probabilistic approach to the understanding and training of neural network classifiers. In Proceedings of the 1990 IEEE international conference on acoustics, speech, and signal processingHampshire, J., Waibel, A., A novel objective function for improved phoneme recognition using time-delay neural networks (1990) IEEE Transactions on Neural Networks, 1 (2), pp. 216-228; Hinton, G.E., Connectionist learning procedures (1989) Artificial Intelligence, 40 (1-3), pp. 185-234; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Møller, M. (1993). Efficient training of feed-forward neural networks. Ph.D. thesis. Computer Science Department - Aarhus UniversityMarques de Sá, J., (2001) Pattern recognition: Concepts, methods and applications, , Springer Verlag; Matsuoka, K., & Yi, J. (1991). Backpropagation based on the logarithmic error function and elimination of local minima. In Proceedings of the 1990 IEEE international joint conference on neural networksRichard, M., Lippmann, R., Neural network classifiers estimate bayesian a posteriori probabilities (1991) Neural Computation, 3, pp. 461-483; Santos, J., Alexandre, L., & Marques de Sá, J. (2004). The error entropy minimization algorithm for neural network classification. In int. conf. on recent advances in soft computingSilva, L., Alexandre, L., Marques de Sá, J., Neural network classification: Maximizing zero-error density (2005) LNCS, 3686, pp. 127-135. , ICAPR 2005; Silva, L., Alexandre, L.A., & Marques de Sá, J. (2006). New developments of the Z-EDM algorithm. In Proceedings of the sixth international conference intelligent systems design and applications: Vol. 1 (pp. 1067-1072)Silva, L., Marques de Sá, J., & Alexandre, L. (2005). Neural network classification using Shannon's entropy. In European symposium on artificial neural networksSilverman, B., (1986) Density estimation for statistics and data analysis, , Chapman & Hall; Solla, S.A., Levin, E., Fleisher, M., Accelerated learning in layered neural networks (1988) Complex Systems, 2 (6), pp. 625-639
Keywords: algorithm; Algorithms; analytical error; article; calculation; Classification; Complementary features; Cybernetics; data analysis; Data classification; Data classifications; Data Interpretation, Statistical; Electric loads; entropy; Error functions; learning; Learning processes; mathematical analysis; Mathematical properties; Models, Statistical; Multilayer neural networks; Multilayer perceptron; Multilayer perceptrons; Multilayers; Neural networks; Neural Networks (Computer); Pattern recognition systems; perceptron; Performance improvements; priority journal; Probability density function

Dissimilarity-based classification of chromatographic profiles - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Pattern Analysis and ApplicationsPattern Anal. Appl., 2008)
This paper proposes a non-parametric method for the classification of thin-layer chromatographic (TLC) images from patterns represented in a dissimilarity space. Each pattern corresponds to a mixture of Gaussian approximation of the intensity profile. The methodology comprises various phases, including image processing and analysis steps to extract the chromatographic profiles and a classification phase to discriminate among two groups, one corresponding to normal cases and the other to three pathological classes. We present an extensive study of several dissimilarity-based approaches analysing the influence of the dissimilarity measure and the prototype selection method on the classification performance. The main conclusions of this paper are that, Match and Profile-difference dissimilarity measures present better results, and a new prototype selection methodology achieves a performance similar or even better than conventional methods. Furthermore, we also concluded that simplest classifiers, such as k-NN and linear discriminant classifiers (LDCs), present good performance being the overall classification error less than 10% for the four-class problem. © 2008 Springer-Verlag London Limited.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1007/s10044-008-0113-2Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto Superior de Engenharia do Porto, Rua Dr. António Bernardino Almeida, 431, 4200-072 Porto, Portugal; email: ats@isep.ipp.ptReferences: Reich, E., Blatter, A., Modern TLC: A key technique for identification and quality control of botanicals and dietary supplements (2004) Inside Laboratory Management-AOC International;Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) LNCS, 3212, pp. 158-165. , Proceedings of image analysis and recognition: international conference, ICIAR 2004, Porto Springer, Heidelberg; Keir, G., Winchester, B.G., Clayton, P., Carbohydrate-deficient glycoprotein syndromes: Inborn errors of protein glycosylation (1999) Ann Clin Biochem, 36, pp. 20-36. , Pt 1; Durand, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clin Chem, 46, pp. 795-805; Schwedt, G., (1997) The Essential Guide to Analytical Chemistry, , Wiley New York; Bajla, I., Hollander, I., Fluch, S., Burg, K., Kollar, M., An alternative method for electrophoretic gel image analysis in the GelMaster software (2005) Comput Methods Programs Biomed, 77, pp. 209-231; Eibrand, R., Kennedy, P., Cotter, D., MacEvilly, U., Wu, B., Analysis of atlantic salmon skin mucus: COPS-a computer-based system for protein pattern analysis of 1D SDS-PAGE gels (2003) Proceedings of the Third IEEE Symposium on Bioinformatics and Bioengeneering; Gerasimov, A.V., Use of the software processing of scanned chromatogram images in quantitative planar chromatography (2004) J Anal Chem, 59, pp. 348-353; (2000) Gel Analysis Software: Important Aspects, , Goulding electrophoresis PN UVItec Ltd; Jedra, M., El Khattabi, N., Limouri, M., Essaid, A., Recognition of seed varieties using a time-delay neural network: Analysis of electrophoretic images (1999) Comput Electron Agric, 22, pp. 1-10; MacHado, A.M.C., Campos, M.F.M., Siqueira, A.M., De Carvalho, O.S.F., An iterative algorithm for segmenting lanes in gel electrophoresis images. Computer graphics and image processing (1997) Proceedings of X Brazilian Symposium, pp. 140-146; Ye, X., Suen, C.Y., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Vision Iterface 99, , Trois-Rivieres, Canada; Wang, D., Keller, J.M., Carson, C.A., Pulsed-field gel electrophoresis pattern recognition of bacterial DNA: A systemic approach (2001) Pattern Anal Appl, 4, pp. 244-255; Shadle, S.E., Allen, D.F., Guo, H., Pogozelski, W.K., Bashkin, J.S., Tullius, T.D., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of a protein-NA binding constant (1997) Nucleic Acids Res, 25, pp. 850-860; Bajla, I., Hollander, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) Measurement Science Review, 1; Bajla, I., Hollander, I., Burg, K., Fluch, S., (2002) A Novel Approach to Quantitative Analysis of Electrophoretic Gel Images of DNA Fragments, pp. 899-902. , IEEE international symposium on biomedical imaging Washington; Lavine, B.K., Meyers, R.A., Clustering and classification of analytical data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , Wiley Chichester; Lonni, A., Scarminio, I., Silva, L., Ferreira, D., Differentiation of species of bacharis genus by HPLC and chemometrics methods (2003) Analytical Sciences, 19; Beltrán, N.H., Duarte-Mermoud, M.A., Salah, S.A., Bustos, M.A., Feature selection algorithms using Chilean wine chromatograms as examples (2005) J Food Eng, 67, pp. 483-490; Landgrebe, D., Information extraction principles and methods for multispectral and hyperspectral image data (1999) Proceedings of Information Processing for Remote Sensing, , World Scientific, Singapore; Landgrebe, D., Hyperspectral image data analysis as a high dimensional signal processing problem (2002) IEEE Signal Process Mag, 19, pp. 17-28; Jimenez, L., Landgrebe, D., Hyperspectral data analysis and feature reduction via projection pursuit (1999) IEEE Trans Geosci Remote Sens, 37, pp. 2653-2667; Jimenez, L.O., Landgrebe, D.A., Supervised classification in high-dimensional space: Geometrical, statistical, and asymptotical properties of multivariate data (1998) IEEE Transaction on Systems Man, and Cybernetics-Part C: Applications and Reviews, 28; Paclik, P., Duin, R.P.W., Dissimilarity-based classification of spectra: Computational issues (2003) Real-Time Imaging, 9, pp. 237-244; Paclik, P., Duin, R.P.W., Classifying spectral data using relational representation (2003) Proceedings of Spectral Imaging Workshop, , Graz; Pekalska, E., Paclik, P., Duin, R.P.W., A generalized kernel approach to dissimilarity-based classification (2001) J Mach Learn Res, 2, pp. 175-211; Pekalska, E., Duin, R.P.W., Dissimilarity representations allow for building good classifiers (2002) Pattern Recogn Lett, 23, pp. 943-956; Pekalska, E., Duin, R.P.W., (2005) The Dissimilarity Representation for Pattern Recognition-foundations and Applications, 64. , World Scientific, Singapore; Pekalska, E., Duin, R.P.W., Paclik, P., Prototype selection for dissimilarity-based classifiers (2006) Pattern Recogn, 39, pp. 189-208; Harol, A., Lai, C., Pekalska, E., Duin, R.P.W., Pairwise feature evaluation for constructing reduced representations (2007) Pattern Anal Appl, 10, pp. 55-68; Dubuisson, M.-P., Jain, A.K., A modified Hausdorff distance for object matching (1994) Proceedings of International Conference on Pattern Recognition, pp. 566-568. , Jerusalem; Heijden, F., Robert, P.W.D., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation, , Wiley, New York; Dasarathy, B.V., Sánchez, J.S., Townsend, S., Nearest neighbour editing and condensing tools-synergy exploitation (2000) Pattern Anal Appl, 3, pp. 19-30; Devijver, P., Kittler, J., (1982) Pattern Recognition: A Statistical Approach, , Prentice-Hall, New Jersey; Cheng, Y., Mean shift, mode seeking, and clustering (1995) IEEE Trans Pattern Anal Mach Intell, 17, pp. 790-799; Vijaya, P.A., Murty, M.N., Subramanian, D.K., Efficient median based clustering and classification techniques for protein sequences (2006) Pattern Anal Appl, 9, pp. 243-255; Sousa, A.V., Mendonça, A.M., Campilho, A., Aguiar, R., Miranda, C.S., Feature extraction for classification of thin-layer chromatography images (2005) Proceedings of Image Analysis and Recognition, Second International Conference, ICIAR 2005, 3656, pp. 974-981. , LNCS Springer, Toronto; Dempster, A., Laird, N., Rubin, D., Maximum likelihood from incomplete data via the em algorithm (1977) J R Stat Soc, B-39, pp. 1-38. , 1; Moré, J.J., Sorensen, D.C., Computing a trust region step (1983) SIAM J Sci Stat Comput, 4, pp. 553-572; Byrd, R.H., Schnabel, R.B., Shultz, G.A., Approximate solution of the trust region problem by minimization over two-dimensional subspaces (1988) Math Program, 40, pp. 247-263; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) Workshop on Learning from Imbalanced Datasets II, , ICML, Washington DC; Sousa, A.V., Mendonça, A.M., Campilho, A.C., The class imbalance problem in TLC image classification (2006) Proceedings of Image Analysis and Recognition, Third International Conference, ICIAR 2006, 4142, pp. 513-523. , September 18-20, 2006, proceedings, Part II, Póvoa de Varzim. LNCS Springer, Portugal
Keywords: Chromatographic images; Dissimilarity representation; Nearest neighbour classifiers; Prototype selection

Frequency domain and entropy analysis of fetal heart rate: Appealing tools for fetal surveillance and pharmacodynamic assessment of drugs - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bemardes, J. (Cardiovascular and Hematological Disorders - Drug TargetsCardiovasc. Hematol. Disord. Drug Targets, 2008)
Recently, frequency domain and entropy analysis of fetal heart rate (FHR) have been assessed in several studies, providing new insights into physiologic regulatory mechanisms, constituting appealing tools for pharmacodynamic assessment, namely during fetal life. There is evidence that entropy and frequency domain analysis convey information on cortical and autonomic nervous system activities, respectively. Use of internal versus external FHR acquisition sensors and the signal sampling frequency may dramatically affect results. Most FHR frequency domain indices are significantly increased with rising fetal activity, namely during active wakefulness and active sleep, whereas the opposite occurs with nonlinear indices. This is in favour of increased activity of the autonomous nervous system and decreased activity of the central nervous system complexity control systems, during periods of fetal activity. Progression of labor is associated with a significant increase in FHR frequency domain indices, whereas entropy indices are significantly decreased. This denotes activation of the autonomic nervous system in the final minutes of labour, associated with decreased central nervous system activity. The emerging knowledge on FHR frequency domain and entropy analysis substantiates a continued interest of these methods in evaluation of the fetal pathophysiologic regulatory mechanisms, and opens new perspectives for clinical and pharmacodynamic assessment. © 2008 Bentham Science Publishers Ltd.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.2174/187152908784533720Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade do Porto, Rua do Campo Alegre 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptChemicals/CAS: atropine, 51-55-8, 55-48-1; betamethasone, 378-44-9; lidocaine, 137-58-6, 24847-67-4, 56934-02-2, 73-78-9; magnesium sulfate, 7487-88-9; opiate, 53663-61-9, 8002-76-4, 8008-60-4; propranolol, 13013-17-7, 318-98-9, 3506-09-0, 4199-09-1, 525-66-6; salbutamol, 18559-94-9References: Task-Force. Heart rate variability. Standards of measurement, physiological interpretation, and clinical use. Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology (1996) Eur. Heart J, 17, pp. 354-381;Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am. J. Physiol. Heart Circ. Physiol, 29, pp. H2560-H2570; Pincus, S.M., Minkin, M.J., Assessing sequential irregularity of both endocrine and heart rate rhythms (1998) Curr. Opin. Obstet. Gynecol, 1 (4), pp. 281-291; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int. J. Gynecol. Obstet, 25, pp. 159-167; American College of Obstetricians and Gynecologists. ACOG Practice Bulletin. Clinical Management Guidelines for Obstetrician-Gynecologists, Number 70, December 2005 (2005) Int. J. Gynecol. Obstet, 1, pp. 1453-1460. , ACOG; (2001) Royal College of Obstetricians and Gynaecologists. Evidence-Based Clinical Guideline Number 8. The Use of Electronic Fetal Monitoring, , RCOG, Royal College of Obstetricians and Gynaecologists: London; International Federation of Gynecology and Obstetrics. Intrapartum surveillance: Recommendations on current practice and overview of new developments. FIGO Study Group on the Assessment of New Technology. International Federation of Gynecology and Obstetrics (1995) Int. J. Gynecol. Obstet, 49 (2), pp. 213-221. , FIGO; National Institute of Child Health and Human Development Research Planning Worlshop. Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am. J. Obstet. Gynecol, 177, pp. 1385-1390. , NICH; Dawes, G.S., Moulden, M., Redman, C.W.G., System 8000 - Computerized antenatal FHR analysis (1991) J. Perinat. Med, 19 (1-2), pp. 47-51; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J. Perinat. Med, 19, pp. 61-65; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Mat. Fet. Med, 9, pp. 311-318; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int. J. Gynecol. Obstet, 2, pp. 141-147; Bernardes, J., Costa-Pereira, A., The effect of different sampling intervals on the measurement of intrapartum fetal heart rate variability. Letter to the Editor (1997) Obstet. Gynecol, 9, pp. 318-319; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br. J. Obstet. Gynecol, 1, pp. 1307-1310; Ayres-de-Campos, D., Bernardes, J., Early, variable and late decelerations: Can a consensus be reached in their identification? (1999) Int. J. Gynecol. Obstet, 5 (3), pp. 305-306; Grant, J.M., The fetal heart rate trace is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Bernardes, J.; Costa-Pereira, A. Efficacy and safety of intrapartum electronic fetal monitoring: An update. Obstet. Gynecol., 1996}, 87 3, 476-477Bernardes, J., Costa-Pereira, A., Admission cardiotocography (2003) Lancet, 3 (1), p. 1741; Alfirevic, Z., Devane, D., Gyte, G.M.L., Continuous cardiotocography (CTG) as a form of electronic fetal monitoring (EFM) for fetal assessment during labour (2006) Coch. Data. Sys. Rev, 3; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet. Gynecol, 79 (2), pp. 249-255; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans. Biomed. Eng, 5 (3), pp. 365-373; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med. Biol. Eng. Comput, 44 (1), pp. 847-855; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum. Dev, 83, pp. 585-591; Parer, J.T., (1997) Handbook of Fetal Heart Rate Monitoring, , W. B. Saunders Company: Philadelphia, Pennsylvania; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin. Obstet. Gynaecol, 8 (3), pp. 643-661; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Uehara, S., Yajima, A., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am. J. Obstet. Gynecol, 182, pp. 1227-1232; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur. J. Obstet. Gynecol. Reprod. Biol, 114, pp. 137-143; Court, D.J., Parer, J.T., In Research in Perinatal Medicine (1984) Experimental studies of fetal asphyxia and fetal heart rate interpretation, pp. 113-169. , Nathanielsz, P.W, Parer, J.T; Eds, Perinatology Press: New York; vanGeijn, H.P., Developments in CTG analysis (1996) Baillieres Clin. Obstet. Gynaecol, 1 (2), pp. 185-209; Bernardes, J., Costa-Pereira, A., A more objective fetal heart rate baseline estimation (1996) Br. J. Obstet. Gynaecol, 1 (3), pp. 714-715; Ayres-de-Campos, D., Bernardes, J., Marsal, K., Nickelsen, C., Makarainen, L., Banfield, P., Xavier, P., Campos, I., Can the reproducibility of fetal heart rate baseline estimation be improved? (2004) Eur. J. Obstet. Gynecol. Reprod. Biol, 112, pp. 49-54; Ayres-de-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto ® multicentre validation study (2005) Eur. J. Obstet. Gynecol. Reprod. Biol, 118 (1), pp. 52-60; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc. Natl. Acad. Sci. USA, 88, pp. 2297-2301; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am. J. Physiol. Heart. Circ. Physiol, 278, pp. H2039-H2049; Fusheng, Y., Bo, H., Qingyu, T., (1998) Nonlinear biomedical signal processing - Volume II: Dynamical analysis and modelling, pp. 72-91. , Ed, Approximate entropy and its application in biosignal analysis; IEEE Press: New York; Pincus, S., Approximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Hayes, M., (1996) Statistical digital signal processing and modelling, , Jonh Wiley and Sons, Inc.:New York; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grossesse et de l'accouchement (2004) Encyclopédie Médico-Chirurgicale, 148, pp. 1-10. , 5.049-D-23; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol. Meas, 27, pp. 307-319; Magenes, G., Signorini, M.G., Arduini, D., Cerutti, S., Fetal heart rate variability due to vibroacoustic stimulation: Linear and nonlinear contribution (2004) Methods Inf. Med, 43 (1), pp. 47-51; Hallak, M.; Martinez-Poyer, J.; Kruger, M.L.; Hassan, S.; Blackwell, S.C.; Sorokin, Y. The effect of magnesium sulfate on fetal heart rate parameters: A randomized, placebo-controlled trial. Am. J. Obstet. Gynecol., 1999, 181 5 Part 1, 1122-1127Swartjes, J.M., van Geijn, H.P., Meinardi, H., Mantel, R., Fetal heart-rate patterns and chronic exposure to antiepileptic drugs (1992) Epilepsia, 33 (4), pp. 721-728; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int. J. Gynecol. Obstet, 57 (1), pp. 33-37; Rotmensch, S., Lev, S., Kovo, M., Efrat, Z., Zahavi, Z., Lev, N., Celentano, C., Ben-Rafael, Z., Effect of betamethasone administration on fetal heart rate tracing: A blinded longitudinal study (2005) Fetal. Diagn. Ther, 2 (5), pp. 371-376; Lunshof, M.S., Boer, K., Wolf, H., Koppen, S., Velderman, J.K., Mulder, E.J.H., Short-term (0-48h) effects of maternal betamethasone administration on fetal heart rate and its variability (2005) Pediatr. Res, 57 (4), pp. 545-549; Beckers, F.; Verheyden, B.; Ramaekers, D.; Swinghedauw, B.; Aubert, A.E. Effects of autonomic blockade on non-linear cardiovascular variability indices in rats. Clin. Exp. Pharmacol. Physiol., 2006, 33 5-, 431-439Georgoulas, G., Stylios, C.D., Groumpos, P.P., Predicting the risk of metabolic acidosis for newborns based on fetal heart rate signal classification using support vector machines (2006) IEEE Trans. Biomed. Eng, 53 (5), pp. 875-884; DiRenzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Indraccolo, R., Cosmi, E.V., Fractal analysis: A new method for evaluating fetal heart rate variability (1996) J. Perinat. Med, 24 (3), pp. 261-269; Felgueiras, C., Marques-de-Sá, J.P., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed. Eng, 3 (2), pp. 197-201;
Keywords: acidemia; adrenergic receptor stimulating agent; alpha adrenergic receptor blocking agent; anticonvulsive agent; article; atropine; autonomic nervous system function; beta adrenergic receptor blocking agent; betamethasone; Cardiotocography; central depressant agent; central nervous system function; cholinergic receptor blocking agent; chronotropism; Computerized analysis; drug effect; drug mechanism; electronic sensor; entropy; External and internal monitoring; Female; Fetal behavioral states; Fetal heart rate (FHR); Fetal monitoring; fetus; fetus heart rate; fetus monitoring; frequency analysis; Frequency domain and entropy analysis; gestation period; Heart rate variability; Heart Rate, Fetal; human; Humans; instrumentation; labor; lidocaine; local anesthetic agent; magnesium sulfate; mathematical computing; methodology; nonhuman; opiate; pharmacodynamics; physiology; Pregnancy; prenatal screening; propranolol; pulse rate; review; salbutamol; signal detection

Hip fractures cluster in space: An epidemiological analysis in Portugal - De Pina, M.F.; Alves, S.M.; Barbosa, M.; Barros, H. (Osteoporosis InternationalOsteoporosis Int., 2008)
Summary: Using Portuguese hospital registers (2000-2002) we calculated age-standardized incidence rates of hip fractures. Spatial clusters of high incidence rates were found, with annual averages (per 100,000 inhabitants) varying from 154.4 to 572.2 and 77.3 to 231.5 for women and men, respectively. Geographic inequalities in the occurrence of hip fractures were also found. Introduction: The aim of this study was to identify spatial patterns in the incidence of hip fracture in Portugal during the period 2000 to 2002. Methods: From the National Hospital Discharge Register, admissions of patients (50 years of age or more) with low-energy hip fracture were selected. Age-standardized incidence rates in relation to the municipality of the patients' place of residence were calculated. Empirical Bayes estimators were used to smooth the local risk and spatial statistics methods were used to identify spatial clusters. Results: Of 25,634 hip fractures in individuals aged 50 years or more caused by low or moderate impact, 19,759 occurred in women (age, mean±SD, 80.6±8.6 years) and 5,875 in men (age 77.7±10.0 years). Incidence rates increased exponentially with age, being higher in women nation-wide (female to male ratio from 1.5 to 5.1). Significant geographic differences were found: the incidence rates (95% CI) varied from 154.4 (153.6-155.3) to 572.2 (569.5-575.0) in women and 77.3 (76.64-78.05) to 231.5 (229.9-233.0) in men per 100,000 inhabitants. Spatial autocorrelation values (Moran index) were 0.56 and 0.45 for women and men, respectively. Conclusion: Spatial clusters (p<0.0001) of high incidences were identified. Geographic differences in incidence rates were about threefold. Some regions had incidence rates as high as some north European countries. The geographic inequalities could be due to environmental or socioeconomic factors, but further investigation needs to be done to confirm this hypothesis. © 2008 International Osteoporosis Foundation and National Osteoporosis Foundation.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: OSINEdoi: 10.1007/s00198-008-0623-1PubMed ID: 18536955Language of Original Document: EnglishCorrespondence Address: De Pina, M. F.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, Porto 4150-180, Portugal; email: fpina@ineb.up.ptReferences: Center, J., Eisman, J., The epidemiology and pathogenesis of osteoporosis (1997) Baillieres Clin Endocrinol Metab, 11, pp. 23-62. , 1;Cooper, C., Melton III, L.J., Marcus, R., Feldman, D., Kelsey, J., Magnitude and Impact of osteoporosis and fractures (1996) Osteoporosis, pp. 419-434. , Academic Press San Diego; Walker-Bone, K., Dennison, E., Cooper, C., Epidemiology of osteoporosis (2001) Rheum Dis Clin North Am, 27, pp. 1-18. , 1; Cummings, S.R., Melton III, L.J., Epidemiology and outcomes of osteoporotic fractures (2002) Lancet, 359, pp. 1761-1767; Cooper, C., Campion, G., Melton, L.J., Hip fractures in the elderly: A world-wide projection (1992) Osteoporos Int, 2, pp. 285-289; Karagas, M.R., Lu-Yao, G.L., Barrett, J.A., Heterogeneity of hip fracture: Age, race, sex, and geographic patterns of femoral neck and trochanteric fractures among the US elderly (1996) Am J Epidemiol, 143, pp. 677-682. , 7; Jordan, K.M., Cooper, C., Epidemiology of osteoporosis (2002) Best Pract Res Clin Rheumatol, 16, pp. 795-806. , 5; Orimo, H., Hashimoto, T., Sakata, K., Trends in the incidence of hip fracture in Japan, 1987-1997: The third nationwide survey (2000) J Bone Miner Metab, 18, pp. 126-131; Kennedy, S., Goodchild, M., Gopal, S., The small number problem and the accuracy of spatial databases (1994) Accuracy of Spatial Databases, pp. 187-196. , Taylor and Francis London; (1995) Interactive Spatial Data Analysis, , Bailey TC, Gatrell AC (eds) Longman, London; Anselin, L., Local indicators of spatial association - LISA (1995) Geogr Anal, 27, pp. 93-115. , 2; Chevalley, T., Herrmann, F.R., Delmi, M., Evaluation of the age-adjusted incidence of hip fractures between urban and rural areas: The difference is not related to the prevalence of institutions for the elderly (2002) Osteoporos Int, 13, pp. 113-118; Sanders, K., Nicholson, G.C., Ugoni, A.M., Fracture rates lower in rural than urban communities: The Geelong Osteoporosis Study (2002) J Epidemiol Community Health, 56, pp. 466-470; Vaz, A.L., Epidemiology and costs of osteoporotic hip fractures in Portugal (1993) Bone, 14, p. 9. , Suppl 1; Lofthus, C.M., Osnes, E.K., Falch, J.A., Epidemiology of hip fractures in Oslo, Norway (2001) Bone, 29, pp. 413-418. , 5; Nydegger, V., Rizzoli, R., Rapin, C.H., Epidemiology of fractures of the proximal femur in Geneva: Incidence, clinical and social aspects (1991) Osteoporos Int, 2, pp. 42-47. , 1; Hernandez, J., Olmos, J.M., Alonso, M.A., Trend in hip fracture epidemiology over a 14-year period in a Spanish population (2006) Osteoporos Int, 17, pp. 464-470; Giversen, I.M., Time trends of age-adjusted incidence rates of first hip fractures: A register-based study among older people in Viborg County, Denmark, 1987-1997 (2006) Osteoporos Int, 17, pp. 552-564; Coster, A., Haberkamp, M., Allolio, B., Incidence of femoral neck fractures in the German Federal Republic in comparison to other countries (1994) Soz Praventivmed, 39, pp. 287-292. , 5; Paspati, I., Galanos, A., Lyritis, G.P., Hip fracture epidemiology in Greece during 1977-1992 (1998) Calcif Tissue Int, 62, pp. 542-547. , 6; Kannus, P., Niemi, S., Parkkari, J., Hip fractures in Finland between 1970 and 1997 and predictions for the future (1999) Lancet, 353, pp. 802-805. , 9155
Keywords: adult; Age Distribution; aged; Aged, 80 and over; article; Bayes Theorem; Bone Density; Cluster Analysis; Databases, Factual; falling; Female; fracture; geographic information system; Geographic information systems; hip fracture; Hip fractures; human; Humans; incidence; international classification of diseases; major clinical study; male; Middle Aged; Osteoporosis; Portugal; priority journal; Risk Factors; sex difference; Sex Distribution; Space-Time Clustering; Spatial analysis; Spatial clusters; Spatial dependency

A hybrid approach for arabidopsis root cell image segmentation - Marcuzzo, M.; Quelhas, P.; Campilho, A.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
In vivo observation and tracking of the Arabidopsis thaliana root meristem, by time-lapse confocal microscopy, is important to understand mechanisms like cell division and elongation. The research herein described is based on a large amount of image data, which must be analyzed to determine the location and state of cells. The automation of the process of cell detection/marking is an important step to provide research tools for the biologists in order to ease the search for special events, such as cell division. This paper discusses a hybrid approach for automatic cell segmentation, which selects the best cell candidates from a starting watershed-based image segmentation and improves the result by merging adjacent regions. The selection of individual cells is obtained using a Support Vector Machine (SVM) classifier, based on the shape and edge strength of the cells' contour. The merging criterion is based on edge strength along the line that connects adjacent cells' centroids. The resulting segmentation is largely pruned of badly segmented and over-segmented cells, thus facilitating the study of cell division. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_73Language of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPPortugalReferences: Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627;Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res, 119, pp. 85-93; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A.: Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo. In: Motion 2007, pp. 13-13 (2007)Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic Tracking of Arabidopsis thaliana Root Meristem in Confocal Microscopy (2004) LNCS, 3212, pp. 166-174. , Campilho, A.C, Kamel, M, eds, ICIAR 2004, Springer, Heidelberg; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Trans. on PAMI, 7 (12), pp. 629-639; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Trans. on Image Processing, 16 (8), pp. 2080-2095; Luc, V., Soille, P., Watersheds in digital spaces: An efficient algorithm based on immersion simulations (1991) IEEE Trans. on PAMI, 13 (6), pp. 583-598; Meyer, F., Beucher, S., Morphological segmentation (1990) JVCIR, 1 (1), pp. 21-46; Bleau, A., Leon, L., Watershed-based segmentation and region merging (2000) Comput. Vis. Image Underst, 77 (3), pp. 317-370; Kovesi, P.: Symmetry and asymmetry from local phase. In: Proc. of the Tenth Australian Joint Conf. on Artificial Intelligence (December 1997)Burges, C., A tutorial on support vector machines for pattern recognition (1998) Data Mining and Knowledge Discovery, 2 (2), pp. 121-167
Keywords: Arabidopsis (Arabidopsis thaliana); Arabidopsis thaliana (ELIP); Cell divisions; Cell image segmentation; cell proliferation; Cell segmentation; Cells; confocal microscopy; Digital image storage; Heidelberg (CO); Hybrid approaches; Image analysis; Image data; image processing; Image segmentation; Imaging techniques; In vivo observation; Individual (PSS 544-7); International conferences; Merging; Microscopic examination; Research tools; Root meristem; Strength (IGC: D5/D6); Support Vector Machine (SVM); Support vector machines; Time lapse confocal microscopy

Hybrid chitosan membranes tested in sheep for guided tissue regeneration - Cortez, P.P.; Shirosaki, Y.; Botelho, C.M.; Simões, M.J.; Gartner, F.; Da Costa, R.M.G.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Maurício, A.C. (Key Engineering MaterialsKey Eng Mat, 2008)
Previous in vitro studies confirmed an improved cytocompatibility of chitosan-silicate hybrid membranes over chitosan membranes. The main goal of this study was to assess the in vivo histocompatibility of both membranes through subcutaneous implantations at different time periods, 1 week, 1, 2 and 3 months, using a sheep model. Chitosan membranes elicited an exuberant inflammatory response and were consequently rejected. The hybrid chitosan membranes were not rejected and the degree of inflammatory response decreased gradually until the third month of implantation. Histological evaluation also showed that these membranes can be resorbed in vivo. This study demonstrates that the incorporation of silicate into the chitosan solution improves its histocompatibility, indicating that the hybrid chitosan-silicate membranes are suitable candidates to be used in clinical applications.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Cortez, P.P.; Centro de Estudos de Ciência Animal (CECA), Instituto de Ciências e Tecnologias Agrárias e Agro-Alimentares (ICETA), Campus Agrário de Vairão, Rua P. Armando Quintas, 4485-661, Vairão, Portugal; email: pcortez@mail.icav.up.ptReferences: Nasser, N.J., Friedman, A., Friedman, M., Moor, E., Mosheiff, R., (2005) Injury, 36, p. 1460;Chandy, T., Sharma, C.P., (1990) Biomater. Artif. Cells Artif. Organs, 18, p. 1; Domard, A., Rinaudo, M., (1983) Int J Biol Macromol, 5, p. 49; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Eng. Mat, 254-256, p. 857; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, p. 485; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Kadosawa, T., Fujinaga, T., (1999) Biomaterials, 20, p. 1407
Keywords: biodegradability; Biodegradable membrane; Biodegradable membranes; chitosan; Chitosan-silicate hybrid; Guided tissue regeneration (GTR); histology; in vivo study; Membranes; Silicates; Tissue culture

The influence of the risk functional in data classification with MLPs - Silva, L.M.; Embrechts, M.; Santos, J.M.; De Sá, J.M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
We investigate the capability of multilayer perceptrons using specific risk functionals attaining the minimum probability of error (optimal performance) achievable by the class of mappings implemented by the multilayer perceptron (MLP). For that purpose we have carried out a large set of experiments using different risk functionals and datasets. The experiments were rigorously controlled so that any performance difference could only be attributed to the different risk functional being used. Statistical analysis was also conducted in a careful way. From the several conclusions that can be drawn from our experimental results it is worth to emphasize that a risk functional based on a specially tuned exponentially weighted distance attained the best performance in a large variety of datasets. As to the issue of attaining the minimum probability of error we also carried out classification experiments using non-MLP classifiers that implement complex mappings and are known to provide the best results until this date. These experiments have provided evidence that at least in many cases, by using an adequate risk functional, it will be possible to reach the optimal performance. © Springer-Verlag Berlin Heidelberg 2008.
Conference code: 73798Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-87536-9_20Language of Original Document: EnglishCorrespondence Address: Silva, L. M.; INEB -Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Rua Dr. Roberto Frias, 4200 - 465 Porto, Portugal; email: lmsilva@fe.up.ptReferences: Silva, L.M., Alexandre, L.A., Marques de Sá, J.: Data classification with multilayer perceptrons using a generalized error function. Neural Networks (2008) doi:10.1016/j.neunet.2008.04,004Erdogmus, D., Principe, J.C., Generalized information potential criterion for adaptive system training (2002) IEEE Transactions on Neural Networks, 13 (5), pp. 1035-1044;Erdogmus, D., Principe, J.C., An Error-Entropy Minimization Algorithm for Supervised Training of Nonlinear Adaptive Systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Santos, J.M., Alexandre, L.A., Marques de Sá, J., The Error Entropy Minimization Algorithm for Neural Network Classification (2004) Int. Conf. on Recent Advances in Soft Computing, , Nottingham, United Kingdom; Duda, R., Hart, P., Stork, D., (2001) Pattern Classification, , Wiley-Interscience, Chichester; Newman, D., Hettich, S., Blake, C., Merz, C., (1998) UCI repository of machine learning databases; Baum, E.B., Haussler, D., What size net gives valid generalization? (1990) Neural Computation, 1 (1), pp. 151-160; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Neural Networks Trained with the EEM Algorithm: Tuning the Smoothing Parameter (2005) WSEAS Transactions on Systems, 4 (4), pp. 295-300; Marques de Sá, J., (2007) Using SPSS, STATISTICA, MATLAB and R, , 2nd edn. Springer, Heidelberg; Embrechts, M.J., Szymanski, B., Sternickel, M., Introduction to Scientific Data Mining: Direct Kernel Methods and Applications (2004) Computationally Intelligent Hybrid Systems, pp. 317-363. , ch. 10, pp, Wiley Interscience, Chichester; Bennett, K.P., Embrechts, M.J., An Optimization Perspective on Kernel Partial Least Squares Regression (2003) Models and Applications. NATO Science Series, 3, pp. 227-249. , Advances in Learning Theory: Methods, 190, pp, IOS Press, Amsterdam; Suykens, J.A.K., Vandewalle, J., Least squares support vector machine classifiers (1999) Neural Processing Letters, 9 (3), pp. 293-300; Suykens, J.A.K., Gestel, T.V., Brabanter, J.D., Moor, B.D., Vandewalle, J., (2003) Least Squares Support Vector Machines, , World Scientific Pub. Co, Singapore; Keerthi, S.S., Shevade, S.K., SMO algorithm for least squares SVM formulations (2003) Neural Computation, 15, pp. 487-507; Cristianini, N., Shawe-Taylor, J., (2000) Support Vector Machines and Other KernelBased Learning Methods, , Cambridge University Press, Cambridge; Vapnik, V., (1998) Statistical Learning Theory, , Wiley-Interscience, Chichester; Schölkopf, B., Smola, A.J., (2002) Learning with Kernels, , MIT Press, Cambridge
Keywords: Backpropagation; Complex mapping; Data classification; Data sets; Electric loads; Experiments; Functionals; Minimum probability of error; MLP classifiers; Multi layer perceptron; Multi-layer perceptrons; Multilayer neural networks; Multilayers; Optimal performance; Pattern recognition systems; Probability density function; risks; Statistical analysis; Weighted distance

Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability - Oliveira, S.M.; Barrias, C.C.; Almeida, I.F.; Costa, P.C.; Pena Ferreira, M.R.; Bahia, M.F.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part B Applied BiomaterialsJ. Biomed. Mater. Res. Part B Appl. Biomater., 2008)
The aim of this study was to test the injectability of a bone filler system based on the combination of ceramic microspheres with a gel-like vehicle, for noninvasive surgery. Porous hydroxyapatite microspheres with a uniform size and an average diameter of 535 ± 38 μm were prepared, and their compression strength and friability were tested. The sodium-alginate solution with a concentration of 7.25% (w/v) was used as the vehicle. To promote its in situ gelation, calcium carbonate and D-gluconic-δ-lactone were added to the solution. Microspheres were mixed with the vehicle at different percentages (20-40 wt %). Gelation times in the range of 8-20 min, were obtained, depending on the formulation. Mixtures of HAp microspheres with alginate solution at 7.25% originating a gel in 11 min present an adequate handling time to perform an injection. Their injectability was evaluated using an injection device commonly employed in vertebroplasty surgical procedures, coupled to a texturometer in compression mode. Using an extrusion rate of 0.1 mm/s, the force required to extrude any of the mixtures tested was lower than 100 N. For an extrusion rate of 1 mm/s mixtures with 40 wt % of microspheres were very difficult to inject. Mixtures with 35 wt % of microspheres presented the best compromise between injectability and compression strength of the gelled system. MicroCT analysis revealed a homogeneous distribution of the microspheres inside the vehicle, as well as full interconnection of the intra-microspheres spaces. The compression strength for the gelled systems ranged from 80 kPa (gel itself) to 600 kPa (composite with 40 Wt % of microspheres). © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JBMRGdoi: 10.1002/jbm.b.31066PubMed ID: 18437700Language of Original Document: EnglishCorrespondence Address: Oliveira, S. M.; Escola Superior de Tecnologia de Viseu (ESTV), Dep. de Eng. Mecânica e Gestão Industrial, 3504-510 Viseu, Portugal; email: serafim@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; calcium carbonate, 13397-26-7, 13701-58-1, 14791-73-2, 471-34-1; gluconolactonase, 9012-44-6, 9012-73-1; hydroxyapatite, 1306-06-5, 51198-94-8; Bone Substitutes; Durapatite, 1306-06-5; GelsTradenames: Captal S, Plasma BiotalManufacturers: Plasma BiotalReferences: Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373;Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev, 12, pp. 115-133; Melton, L.J., Melton, L.J., Kan, S.H., Frye, M.A., Wahner, H.W., O'Fallon, W.M., Riggs, B.L., Epidemiology of vertebral fractures in women (1989) Am J Epidemiol, 129, pp. 1000-1011; Carrodeguas, R.G., Lasa, B.V., Del Barrio, J.S., injectable acrylic bone cements for vertebroplasty with improved properties (2004) J Biomed Mater Res B Appl Biomater, 68, pp. 94-104; Hee, H.T., Percutaneous vertebroplasty: Current concepts and local experience (2005) Neurol India, 53, pp. 475-482; Hide, I.G., Gangi, A., Percutaneous vertebroplasty: History, technique and current perspectives (2004) Clin Radiol, 59, pp. 461-467; Verlaan, J.J., Oner, F.C., Verbout, A.J., Dhert, W.J., Temperature elevation after vertebroplasty with polymethylmethacrylate in the goat spine (2003) J Biomed Mater Res B Appl Biomater, 67, pp. 581-585; Hardouin, P., Grados, F., Cotten, A., Cortet, B., Should percutaneous vertebroplasty be used to treat osteoporotic fractures? An update (2001) Joint Bone Spine, 68, pp. 216-221; Berlemann, U., Ferguson, S.J., Nolte, L.P., Heini, P.F., Adjacent vertebral failure after vertebroplasty. A biomechanical investigation (2002) J Bone Joint Surg Br, 84, pp. 748-752; Wilcox, R.K., The biomechanical effect of vertebroplasty on the adjacent vertebral body: A finite element study (2006) Proc Inst Mech Eng [H], 220, pp. 565-572; Uppin, A.A., Hirsch, J.A., Centenera, L.V., Pfiefer, B.A., Pazianos, A.G., Choi, I.S., Occurrence of new vertebral body fracture after percutaneous vertebroplasty in patients with osteoporosis (2003) Radiology, 226, pp. 119-124; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Bioceramics, 254, pp. 877-880; Becker, T.A., Kipke, D.R., Brandon, T., Calcium alginate gel: A biocompatible and mechanically stable polymer for endovascular embolization (2001) J Biomed Mater Res, 54, pp. 76-86; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Steinert, A., Weber, M., Dimmler, A., Julius, C., Schutze, N., Noth, U., Cramer, H., Hendrich, C., Chondrogenic differentiation of mesenchymal progenitor cells encapsulated in ultrahigh-viscosity alginate (2003) J Orthop Res, 21, pp. 1090-1097; Wang, L., Shelton, R.M., Cooper, P.R., Lawson, M., Triffitt, J.T., Barralet, J.E., Evaluation of sodium alginate for bone marrow cell tissue engineering (2003) Biomaterials, 24, pp. 3475-3481; Shapiro, L., Cohen, S., Novel alginate sponges for cell culture and transplantation (1997) Biomaterials, 18, pp. 583-590; Eiselt, P., Yeh, J., Latvala, R.K., Shea, L.D., Mooney, D.J., Porous carriers for biomedical applications based on alginate hydrogels (2000) Biomaterials, 21, pp. 1921-1927; Wee, S., Gombotz, W.R., Protein release from alginate matrices (1998) Adv Drug Deliv Rev, 31, pp. 267-285; Draget, K.I., Skjak-Braek, G., Smidsrod, O., Alginate based new materials (1997) Int J Biol Macromol, 21, pp. 47-55; Bajpai, S.K., Sharma, S., Investigation of swelling/degradation behaviour of alginate beads crosslinked with Ca2+ and Ba2+ ions (2004) React Funct Polym, 59, pp. 129-140; Ouwerx, C., Velings, N., Mestdagh, M.M., Axelos, M.A.V., Physico-chemical properties and rheology of alginate gel beads formed with various divalent cations (1998) Polym Gels Networks, 6, pp. 393-408; Paul, W., Sharma, C.P., Development of porous spherical hydroxyapatite granules: Application towards protein delivery (1999) J Mater Sci Mater Med, 10, pp. 383-388; Jarcho, M., Calcium-phosphate ceramics as hard tissue prosthetics (1981) Clin Orthop Relat Res, 157, pp. 259-278; Uda, H., Sugawara, Y., Nakasu, M., Experimental studies on hydroxyapatite powder-carboxymethyl chitin composite: Injectable material for bone augmentation (2006) Br J Plast Surg, 59, pp. 188-196; Xu, H.H., Weir, M.D., Burguera, E.F., Fraser, A.M., Injectable and macroporous calcium phosphate cement scaffold (2006) Biomaterials, 27, pp. 4279-4287; Weiss, P., Gauthier, O., Bouler, J.M., Grimandi, G., Daculsi, G., Injectable bone substitute using a hydrophilic polymer (1999) Bone, 25, pp. 67S-70S; Iooss, P., Le Ray, A.M., Grimandi, G., Daculsi, G., Merle, C., A new injectable bone substitute combining poly(epsilon-caprolactone) microparticles with biphasic calcium phosphate granules (2001) Biomaterials, 22, pp. 2785-2794; Gauthier, O., Khairoun, I., Bosco, J., Obadia, L., Bourges, X., Rau, C., Magne, D., Weiss, P., Noninvasive bone replacement with a new injectable calcium phosphate biomaterial (2000) J Biomed Mater Res A, 66, pp. 47-54; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering, Part 1: Structure, gelation rate and mechanical properties (2001) Biomaterials, 22, pp. 511-521; Oakenfull, D., Scott, A., Stabilization of gelatin by sugars and polyols (1986) Food Hydrocolloyds, 1, pp. 163-175; Poon, C.Y., Tonicity, O., Osmolality and Osmolarity (2006) Philadelphia: The Science and Practice of Pharmacy, pp. 250-265. , 21st ed; Gauthier, O., Bouler, J.M., Weiss, P., Bosco, J., Aguado, E., Daculsi, G., Short-term effects of mineral particle sizes on cellular degradation activity after implantation of injectable calcium phosphate biomaterials and the consequences for bone substitution (1999) Bone, 25, pp. 71S-74S; Gisep, A., Curtis, R., Hanni, M., Suhm, N., Augmentation of implant purchase with bone cements: An in vitro study of injectability and dough distribution (2006) J Biomed Mater Res B Appl Biomater, 77, pp. 114-119; Ginebra, M.P., Rilliard, A., Fernandez, E., Elvira, C., San Roman, J., Planell, J.A., Mechanical and rheological improvement of a calcium phosphate cement by the addition of a polymeric drug (2001) J Biomed Mater Res, 57, pp. 113-118; Krebs, J., Ferguson, S.J., Bohner, M., Baroud, G., Steffen, T., Heini, P.F., Clinical measurements of cement injection pressure during vertebroplasty (2005) Spine, 30, pp. E118-E122; Bohner, M., Baroud, G., Injectability of calcium phosphate pastes (2005) Biomaterials, 26, pp. 1553-1563; Hernandez, L., Gurruchaga, M., Goni, I., Influence of powder particle size distribution on complex viscosity and other properties of acrylic bone cement for vertebroplasty and kyphoplasty (2006) J Biomed Mater Res B Appl Biomater, 77, pp. 98-103; Yoshimine, F., Latta, L.L., Milne, E.L., Sliding characteristics of compression hip screws in the intertrochanteric fracture: A clinical study (1993) J Orthop Trauma, 7, pp. 348-353; Jasper, L.E., Deramond, H., Mathis, J.M., Belkoff, S.M., Material properties of various cements for use with vertebroplasty (2002) J Mater Sci Mater Med, 13, pp. 1-5
Keywords: Alginate; alginic acid; Apatite; article; Average diameter; bioengineering; Bone; bone filler system; Bone Substitutes; Calcium; Calcium carbonate; Ceramic; Ceramic microspheres; Coagulation; Colloids; compression; Compression mode; Compression strengths; Compressive Strength; Computerized tomography; Concentration (process); Data compression; Durapatite; Extrusion; Extrusion rates; Fillers; Forming; Gel-forming ability; Gelation; Gels; gluconolactonase; Handling time; Homogeneous distribution; hydrogel; hydroxyapatite; In situ gelation; in situ hybridization; In-situ; Injectability; injection; Injection (oil wells); Micro-CT; microsphere; Microspheres; Mixtures; non invasive procedure; Particle Size; Porous hydroxyapatite; Sodium; Surgery; Surgical procedures; Uniform size; Vehicles; Vertebroplasty

Jaw avascular osteonecrosis after treatment of multiple myeloma with zoledronate - Lobato, J.V.; Maurício, A.C.; Rodrigues, J.M.; Cavaleiro, M.V.; Cortez, P.P.; Xavier, L.; Botelho, C.; Hussain, N.S.; Santos, J.D. (Journal of Plastic, Reconstructive and Aesthetic SurgeryJ. Plast. Reconstr. Aesthetic Surg., 2008)
Purpose: Multiple myeloma, the second most common haematopoietic cancer, which represents the collection of plasma-cell neoplasms that invariably becomes fatal when self-renewing myeloma cells begin unrestrained proliferation. The major clinical manifestation of multiple myeloma is related to the loss of bone through osteolysis. This can lead to pathologic fractures, spinal cord compression, hypercalcaemia, and pain. It is also a major cause of morbidity and mortality in these patients, who frequently require radiation therapy, surgery and analgesic medications. Bisphosphonates are specific inhibitors of osteoclastic activity, and are currently used to prevent bone complications and to treat malignant hypercalcaemia in patients with multiple myeloma, or bone metastases from breast and prostate cancers. Hence, osteonecrosis of the mandible has been reported in three patients from Centro Hospitalar de Vila Nova de Gaia (CHVNG) with multiple myeloma treated for over 18-48 months with intravenous zoledronate, commonly prescribed for multiple myeloma therapy. Although, this report alerts clinicians about the potential complication of bone necrosis in patients receiving bisphosphonate therapy, many questions remain concerning the underlying pathogenesis of this process. Patients and methods: The medical and dental records of three patients with multiple myeloma, who were treated in CHVNG in the past 4 years, were reviewed. These three patients presented exposed bone and osteonecrosis of the mandible, and shared one common clinical feature: all of them were treated with bisphosphonate zoledronate, administered intravenously for long periods. Sequential orthopantomograms (OPGs) and histological evaluation have been analysed from the biopsies of the non healing dental extraction sites of these patients. Results: After a routine dental extraction, these patients developed avascular osteonecrosis of the mandible and secondary bone infection with Actinomyces israelii (actinomycotic osteomyelitis), with no evidence of metastatic disease evaluated by biopsy. In these three described clinical cases, surgical debridment without flap elevation, intensive antibiotherapy and the suspension of the zoledronate treatment allowed a partial recovery of the patients. The purpose of this clinical report is to point out that patients suffering from multiple myeloma can develop bone osteonecrosis induced by treatment with bisphosphonates. Research to determine the mechanism of this dental phenomenon is needed to fully validate and substantiate the possible link between bisphosphonate treatment of multiple myeloma or other cancer diseases and avascular osteonecrosis of the jaws. Until then, clinicians involved in the care of patients at risk should consider this possible complication. © 2006 British Association of Plastic, Reconstructive and Aesthetic Surgeons.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.bjps.2006.06.016PubMed ID: 18068658Language of Original Document: EnglishCorrespondence Address: Maurício, A.C.; Centro de Estudos de Ciência Animal (CECA), Instituto de Ciências, Tecnologias Agrárias e Agro-Alimentares (ICETA), Campus Agrario Vairao, Rua Padre Armando Quintas, 4485-661 Vairão, Portugal; email: ana.colette@mail.icav.up.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; cyclophosphamide, 50-18-0; cyclosporin, 79217-60-0; dexamethasone, 50-02-2; erythropoietin, 11096-26-7; thalidomide, 50-35-1; zoledronic acid, 118072-93-8, 131654-46-1, 165800-06-6, 165800-07-7; Bone Density Conservation Agents; Diphosphonates; Imidazoles; zoledronic acid, 118072-93-8References: Mundy, G.R., Bertoline, D.R., Bone destruction and hypercalcemia in plasma cell myeloma (1986) Semin Oncol, 13 (3), pp. 291-299;Belch, A.R., Bergsagel, D.E., Wilson, K., Effect of daily etidronate on the osteolysis of multiple myeloma (1991) J Clin Oncol, 9 (8), pp. 1397-1402; Kyle, R.A., Jowsey, J., Kelly, P.J., Multiple myeloma bone disease. The comparative effect of sodium fluoride and calcium carbonate or placebo (1975) N Engl J Med, 293 (26), pp. 1334-1338; Kyle, R.A., Multiple myeloma: review of 869 cases (1975) Mayo Clin Proc, 50 (1), pp. 29-40; Roodman, G.D., Pathogenesis of myeloma bone disease (2004) Blood Cells Mol Dis, 32 (2), pp. 290-292; Berenson, J.R., Myeloma bone disease (2005) Best Pract Res Clin Haematol, 18 (4), pp. 653-672; Ruggerio, S.L., Mekrotra, B., Rosenberg, T.J., Osteonecrosis of the jaws associated with the use of bisphosphonates: a review of 63 cases (2004) J Oral Maxillofac Surg, 62, pp. 527-534; Rodan, G.A., Fleisch, H.A., Bisphosphonates: mechanism of action (1996) J Clin Invest, 97 (12), pp. 2692-2696; Coleman, R.E., Metastatic bone disease: clinical features, pathophysiology and treatment strategies (2001) Cancer Treat Rev, 27 (3), pp. 165-176; Sietsema, W.K., Ebetino, F.H., Salvagno, A.M., Antiresorptive dose-response relationship across three generations of bisphosphonates (1989) Drugs Exp Clin Res, 15 (9), pp. 389-396; Schenk, R., Eggli, P., Fleisch, H., Quantitative morphometric evaluation of the inhibitory activity of new amino-bisphosphonates on bone resorption in the rat (1986) Calcif Tissue Int, 38, pp. 342-349; Jung, A., Bisaz, S., Fleisch, H., The binding of pyrophosphate and two diphosphonates by hydroxyapatite crystals (1973) Calcif Tissue Res, 11 (4), pp. 269-280; Coukell, A.J., Markham, A., Pamidronate. A review of its use in the management of osteolytic bone metastases, tumor-induced hypercalcaemia and Paget's disease of bone (1998) Drugs Aging, 12 (2), pp. 149-168; Hughes, D.E., MacDonald, B.R., Russel, R.G.G., Inhibition of osteoclast-like cell formation by bisphosphonates in long-term cultures of human bone marrow (1989) J Clin Invest, 83 (6), pp. 1930-1935; Hughes, D.E., Wright, K.R., Uy, H.L., Bisphosphonates promote apoptosis in murine osteoclasts in vitro and in vivo (1995) J Bone Miner Res, 10 (10), pp. 1478-1487; Murakami, H., Takahashi, N., Sasaki, T., A possible mechanism of the specific action of bisphosphonates on osteoclasts: tiludronate preferentially affects polarized osteoclasts having ruffled borders (1995) Bone, 17 (2), pp. 137-144; Sahni, M., Guenther, H.L., Fleisch, H., Bisphosphonates act on rat bone resorption through the mediation of osteoblasts (1993) J Clin Invest, 91 (5), pp. 2004-2011; Fleisch, H., Bisphosphonates: mechanisms of action (1998) Endocr Rev, 19 (1), pp. 80-100; Shinoda, H., Adamek, G., Félix, R., Structure-activity relationships of various bisphosphonates (1983) Calcif Tissue Int, 35 (1), pp. 87-99; Pereira, J., Mancini, I., Walker, P., The role of bisphosphonates in malignant bone pain: a review (1998) J Palliat Care, 14 (2), pp. 25-36; Purohit, O.P., Radstone, C.R., Anthony, C., A randomized double-blind comparison of intravenous pamidronate and clodronate in the hypercalcemia of malignancy (1995) Br J Cancer, 72 (5), pp. 1289-1293; Hillner, B.E., Ingle, J.N., Chlebowski, R.T., American Society of Clinical Oncology 2003 update on the role of bisphosphonates and bone health issues in women with breast cancer (2003) J Clin Oncol, 21 (21), pp. 4042-4057. , [Erratum in J Clin Oncol 2004;22(7):1351]; Hillner, B.E., Ingle, J.N., Berenson, J.R., American Society of Clinical Oncology guideline on the role of bisphosphonates in breast cancer. American Society of Clinical Oncology Bisphosphonates Expert Panel (2000) J Clin Oncol, 18 (6), pp. 1378-1391; Lacerna, L., Hohneker, J., Zoledronic acid for the treatment of bone metastases in patients with breast cancer and other solid tumours (2003) Semin Oncol, 30 (5 SUPPL. 16), pp. 150-160; Lipton, A., Costa, L., Ali, S., Use of markers of bone turnover for monitoring bone metastases and the response to therapy (2001) Semin Oncol, 28 (4 SUPPL. 11), pp. 54-59; Brincker, H., Westin, J., Abildgaard, N., Failure of oral pamidronate to reduce skeletal morbidity in multiple myeloma: a double-blind placebo-controlled trial. Danish-Swedish Co-operative Study Group (1998) Br J Haematol, 101 (2), pp. 3280-3286; Berenson, J.R., Lichtenstein, A., Porter, L., Long-term pamidronate treatment of advanced multiple myeloma patients reduces skeletal events. Myeloma Aredia Study Group (1998) J Clin Oncol, 16 (7), pp. 593-602; Berenson, J.R., Vescio, R.A., Lee, S.R., Phase I dose-ranging trial of monthly infusions of zoledronic acid for the treatment of osteolytic bone metastases (2001) Clin Cancer Res, 7 (3), pp. 478-485; Van Poznak, C.H., The use of bisphosphonates in patients with breast cancer (2002) Cancer Control, 9 (6), pp. 480-489; Marx, R.E., Pamidronate (Aredia) and zoledronate (Zometa) induced avascular necrosis of the jaws: a growing epidemic (2003) J Oral Maxillofac Surg, 61 (9), pp. 1115-1117; Vannucchi, A.M., Ficarra, G., Antonioli, E., Osteonecrosis of the jaw associated with zoledronate therapy in patient with multiple myeloma (2005) Br J Haematol, 128 (6), pp. 738-739; Wang, J., Goodger, N.M., Pogrel, M.A., Osteonecrosis of the jaws associated with cancer chemotherapy (2003) J Oral Maxillofac Surg, 61 (9), pp. 1104-1107; Purcell, P.M., Boyd, I.W., Bisphosphonates and osteonecrosis of the jaw (2005) Med J Aust, 182 (8), pp. 417-418; Carter, G., Goss, A.N., Doecke, C., Bisphosphonates and avascular necrosis of the jaw: a possible association (2005) Med J Aust, 182 (8), pp. 413-415; Durie, B., Katz, M., Crowley, J., Osteonecrosis of the jaw and bisphosphonates (2005) N Engl J Med, 353, pp. 99-102; Migliorati, C.A., Bisphosphonates and oral cavity avascular bone necrosis (2003) J Clin Oncol, 21 (22), pp. 4253-4254; Robinson, N.A., Yeo, J.F., Bisphosphonates - a word of caution (2004) Ann Acad Med Singapore, 33 (4), pp. 48-49; Starck, W.J., Epker, B.N., Failure of osseointegrated dental implants after diphosphonate therapy for osteoporosis: a case report (1995) Int J Oral Maxillofac Implants, 10 (1), pp. 74-78; Melo, M., Obeid, G., Osteonecrosis of the maxilla in a patient with a history of bisphosphonate therapy (2005) J Can Dent Assoc, 71 (2), pp. 111-113
Keywords: Actinomyces israelii; adult; aged; amoxicillin; antibiotic therapy; article; avascular necrosis; Avascular osteonecrosis; biopsy; Bisphosphonates; Bone Density Conservation Agents; case report; clinical feature; cyclophosphamide; cyclosporin; dexamethasone; Diphosphonates; drug induced disease; drug inhibition; drug withdrawal; erythropoietin; Female; histology; human; Humans; hypercalcemia; Imidazoles; Jaw; jaw avascular osteonecrosis; male; Mandibular Diseases; morbidity; mortality; Multiple myeloma; osteolysis; Osteonecrosis; pain; panoramic radiography; pathologic fracture; priority journal; Radiography, Panoramic; risk assessment; spinal cord compression; thalidomide; tooth extraction; zoledronic acid

Joint detection of the carotid boundaries in longitudinal B-mode images - Rocha, R.; Campilho, A.; Silva, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper proposes a new approach for the automatic segmentation of the carotid adventitia in longitudinal B-scans, with and without the presence of plaque. The top and bottom adventitia contours are jointly detected with a 3D dynamic programing scheme that searches for the best pair of boundaries according to a specified fuzzy cost function. Some discriminating features of the adventitia in B-mode images are used to reduce the attraction by other edges. The final contours are filtered with a smoothing spline fitting. The proposed approach was quantitatively evaluated in a set of 38 images. In order to avoid high correlation of the results, a maximum of two images was selected from each patient. The carotid boundaries manually traced by a medical expert were used as the ground truth. Several statistics show that the proposed algorithm gives good results in most of the cases, including many poor quality images. Examples of the detected contours are presented and compared with the ground truth. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_75Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, PortugalReferences: Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett, 24 (4-5), pp. 757-777;Sonka, M., Liang, W., Stefancik, R., Stolpen, A., Handbook of Medical Imaging: Medical Image Processing and Analysis (2000) SPIE, 2; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Computers in Cardiology, 297-300; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imag, 19 (2), pp. 127-142; Cheng, D., Jiang, X., Schmidt-Trucksass, A., Cheng, K., Automatic intima-media thickness measurement of carotid artery wall in B-mode sonographic images (2006) IEEE International Symposium on Biomedical Imaging (ISBI, pp. 912-915. , IEEE, Los Alamitos; Halenka, M., (1999) Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography, 142, pp. 7-12. , Acta- Universitatis Palackianae Olomucensis Facultatis Medicae; Yu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Processing, 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Processing, 13 (12), pp. 1640-1655; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Analysis and Machine Intelligence, 8 (6), pp. 679-698; Guo, Z., Hall, R.W., Parallel thinning with two-subiteration algorithms (1989) Commun. ACM, 32 (3), pp. 359-373; Black, M.J., Sapiro, G., Marimont, D.H., Heeger, D., Robust anisotropic diffusion (1998) IEEE Trans. Image Processing, 7 (3), pp. 421-432; Tauber, C., (2005) Filtrage anisotrope robuste et segmentation par B-spline snake: Application aux images échographiques, , PhD thesis, Institut National Polytechnique de Toulouse, Toulouse Février; de Boor, C., (1978) A Practical Guide to Splines, , Springer, Heidelberg
Keywords: Automatic segmentations; B-Mode imaging; Edge detection; Fuzzy costs; Ground truth; Heidelberg (CO); Image analysis; Image enhancement; Imaging techniques; International conferences; Joint detection (JD); Medical experts; New approaches; Regression analysis; Smoothing splines

LEGClust - A clustering algorithm based on layered entropic subgraphs - Santos, J.M.; De Sá, J.M.; Alexandre, L.A. (IEEE Transactions on Pattern Analysis and Machine IntelligenceIEEE Trans Pattern Anal Mach Intell, 2008)
Hierarchical clustering is a stepwise clustering method usually based on proximity measures between objects or sets of objects from a given data set. The most common proximity measures are distance measures. The derived proximity matrices can be used to build graphs, which provide the basic structure for some clustering methods. We present here a new proximity matrix based on an entropic measure and also a clustering algorithm (LEGClust) that builds layers of subgraphs based on this matrix, and uses them and a hierarchical agglomerative clustering technique to form the clusters. Our approach capitalizes on both a graph structure and a hierarchical construction. Moreover, by using entropy as a proximity measure we are able, with no assumption about the cluster shapes, to capture the local structure of the data, forcing the clustering method to reflect this structure. We present several experiments on artificial and real data sets that provide evidence on the superior performance of this new algorithm when compared with competing ones. © 2007 IEEE.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: ITPIDdoi: 10.1109/TPAMI.2007.1142Language of Original Document: EnglishCorrespondence Address: Santos, J.M.; Department of Mathematics, ISEP - Polytechnic School of Engineering, R. Dr. A. Bernardino de Almeida 431, 4200-072 Porto, Portugal; email: jms@isep.ipp.ptReferences: Jain, A.K., Dubes, R.C., (1988) Algorithms for Clustering Data, , Prentice Hall International;Jain, A.K., Murty, M.N., Flynn, P.J., Data clustering: A review (1999) ACM Computing Surveys, 31 (3), pp. 264-323; Jain, A., Topchy, A., Law, M., Buhmann, J., Landscape of clustering algorithms (2004) 17th International Conference on Pattern Recognition, 1, pp. 260-263; Berkhin, P., (2002) Survey of clustering data mining techniques, , Accrue Software, San Jose, CA, Tech. Rep; Guha, S., Rastogi, R., Shim, K., CURE: An efficient clustering algorithm for large databases (1998) ACM SIGMOD International Conference on Management of Data, pp. 73-84; Guha, S., Rastogi, R., Shim, K., ROCK: A robust clustering algorithm for categorical attributes (2000) Information Systems, 25 (5), pp. 345-366; Kaufman, L., Rousseeuw, P., (1990) Finding Groups in Data: An Introduction to Cluster Analysis, , New York, NY: John Wiley and Sons; Zhang, T., Ramakrishnan, R., Livny, M., BIRCH: An efficient clustering method for very large databases (1996) ACM SIGMOD Workshop on Research Issues on Data Mining and Knowledge Discovery, pp. 103-114. , Montreal, Canada; Zhang, T., Ramakrishnan, R., Livny, M., BIRCH: A new data clustering algorithm and its applications (1997) Data Mining and Knowledge Discovery, 1 (2), pp. 141-182; Karypis, G., Han, E.-H.S., Kumar, V., Chameleon: Hierarchical clustering using dynamic modeling (1999) IEEE Computer, 32 (8), pp. 68-75; Kamvar, S.D., Klein, D., Manning, C.D., Interpreting and extending classical agglomerative clustering algorithms using a model-based approach (2002) Proceedings of the Nineteenth International Conference on Machine Learning, pp. 283-290. , San Francisco, CA, USA: Morgan Kaufmann Publishers Inc; Johnson, E.L., Mehrotra, A., Nemhauser, G.L., Min-cut clustering (1993) Mathematical Programming, 62, pp. 133-151; Matula, D., Cluster analysis via graph theoretic techniques (1970) Proc. Luisiana Conference on Combinatorics, Graph Theory and Computing, pp. 199-212. , R.C.Mullin, K.B.Reid, and D.P.Roselle, Eds. University of Manitoba, Winnipeg; Matula, D., k-components, clusters and slicings in graphs (1972) SIAM J. Appl. Math, 22 (3), pp. 459-480; Hartuv, E., Schmitt, A., Lange, J., Meier-Ewert, S., Lehrachs, H., Shamir, R., An algorithm for clustering cDNAs for gene expression analysis (1999) RECOMB, pp. 188-197; Hartuv, E., Shamir, R., A clustering algorithm based on graph connectivity (2000) Information Processing Letters, 76 (4-6), pp. 175-181; Wu, Z., Leahy, R., An optimal graph theoretic approach to data clustering: Theory and its application to image segmentation (1993) IEEE Transactions on Pattern Analysis and Machine Learning, 15 (11), pp. 1101-1113; G. Karypis and V. Kumar, Multilevel algorithms for multi-constraint graph partitioning, University of Minnesota, Department of Computer Science/Army HPC Research Center, Minneapolis, Tech. Rep. 98-019, May 1998Fiedler, M., A property of eigenvectors of nonnegative symmetric matrices and its application to graph theory (1975) Czechoslovak Mathematical Journal, 25 (100), pp. 619-633; Chung, F.R.K., (1997) Spectral Graph Theory, (92). , Providence, RI: American Mathematical Society; Shi, J., Malik, J., Normalized cuts and image segmentation (2000) IEEE Transactions on Pattern Analysis and Machine Intelligence, 22 (8), pp. 888-905; Kannan, R., Vempala, S., Vetta, A., On clusterings: Good, bad, and spectral (2000) Proceedings of the 41st Annual Symposium on the Foundation of Computer Science, pp. 367-380; Ding, C., He, X., Zha, H., Gu, M., Simon, H., A min-max cut algorithm for graph partitioning and data clustering (2001) International Conference on Data Mining, pp. 107-114; Ng, A.Y., Jordan, M.I., Weiss, Y., On spectral clustering: Analysis and an algorithm (2001) Advances in Neural Information Processing Systems, 14; Meila, M., Shi, J., A random walks view of spectral segmentation (2001) Eighth International Workshop on Artificial Intelligence and Statistics; Verma, D., Meila, M., (2003) A comparison of spectral clustering algorithms, , Washington University, Tech. Rep. UW-CSE-03-05-01; Ester, M., Kriegel, H.-P., Sander, J., Xu, X., A density-based algorithm for discovering clusters in large spatial databases with noise (1996) 2nd International Conference on Knowledge Discovery and Data Mining, pp. 226-231. , A. Press, Ed; Fukunaga, K., Hostetler, L.D., The estimation of the gradient of a density function, with applications in pattern recognition (1975) IEEE Trans. in Information Theory, 21, pp. 32-40; Cheng, Y., Mean shift, mode seeking, and clustering (1995) IEEE Trans. on Pattern Analysis and Machine Intelligence, 17 (8), pp. 790-799; Comaniciu, D., Meer, P., Mean shift analysis and applications (1999) IEEE International Conference on Computer Vision, pp. 1197-1203; Comaniciu, D., Meer, P., Mean shift: A robust approach toward feature space analisys (2002) IEEE Trans. on Pattern Analysis and Machine Intelligence, 24 (5), pp. 603-619; Fischer, B., Zöller, T., Buhmann, J.M., Path based pairwise data clustering with application to texture segmentation (2001) LNCS - Proceed. of International Workshop on Energy Minimization Methods in Computer Vision and Pattern Recognition, 2134, pp. 235-250; Fischer, B., Buhmann, J.M., Path-based clustering for grouping of smooth curves and texture segmentation (2003) IEEE Transactions on Pattern Analysis and Machine Intelligence, 25 (4), pp. 513-518; Shannon, C., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423,623-656; Renyi, A., Some fundamental questions of information theory (1976) Selected Papers of Alfred Renyi, 2, pp. 526-552; Parzen, E., On the estimation of a probability density function and mode (1962) Annals of Mathematical Statistics, 33, pp. 1065-1076; Xu, D., Príncipe, J., Training mlps layer-by-layer with the information potential (1999) Intl. Joint Conf. on Neural Networks, pp. 1716-1720; H. Li, K. Zhang, and T. Jiang, Minimum entropy clustering and applications to gene expression analysis, in IEEE Computational Systems Bioinformatics Conference, IEEE, Ed., 2004, pp. 142-151Hero, A.O., Ma, B., Michel, O.J., Gorman, J., Applications of entropic spanning graphs (2002) IEEE Signal Processing Magazine, 19 (5), pp. 85-95; Cheng, C.H., Fu, A.W., Zhang, Y., Entropy-based subspace clustering for mining numerical data (1999) International Conference on Knowledge Discovery and Data Mining; Jenssen, R., Hild, I., Erdogmus, K.E.D., Príncipe, J., Eltoft, T., Clustering using renyi's entropy (2003) Proceedings of the International Joint Conference on Neural Networks, pp. 523-528; Gokcay, E., Príncipe, J.C., Information theoretic clustering (2002) IEEE Transactions on Pattern Analysis and Machine Learning, 24 (2), pp. 158-171; Lee, Y., Choi, S., Minimum entropy, k-means, spectral clustering (2004) IEEE International Joint Conference on Neural Networks, 1, pp. 117-122; Lee, Y., Maximum within-cluster association (2005) Pattern Recognition Letters, 26 (10), pp. 1412-1422. , July; J. M. Santos and J. Marques de Sá, Human clustering on bi-dimensional data: An assessment, INEB - Instituto de Engenharia Biomédica, Porto, Portugal, Technical Report 1, October 2005. [Online]. Available: http://www.fe.up.pt/~nnig/papers/ JMS_TechReport2005_1.pdfSilverman, B.W., (1986) Density Estimation for Statistics and Data Analisys, 26. , Chapman & Hall; Bowman, A.W., Azzalini, A., (1997) Applied Smooting Techniques for Data Analysis, , London: Oxford University Press; Jenssen, R., Eltoft, T., Príncipe, J., Information theoretic spectral clustering (2004) Proceedings of the International Joint Conference on Neural Networks, pp. 111-116; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Neural Networks Trained with the EEM Algorithm: Tuning the Smoothing Parameter (2005) 6th WSEAS Int. Conf. on Neural Networks; Proença, H., Alexandre, L.A., UBIRIS: A noisy iris image database (2005) Proceed. of ICIAP 2005 - Intern. Confer. on Image Analysis and Processing, 1, pp. 970-977; (2000), http:// genome-www.stanford.edu/nci60, Stanford NCI60 cancer microarray projectBlake, C., Keogh, E., Merz, C., (1998) UCI repository of machine learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Forina, M., Armanino, C., Eigenvector projection and simplified nonlinear mapping of fatty acid content of italian olive oils (1981) Ann. Chim. (Rome), 72, pp. 127-155; G. Karypis, Cluto: Software package for clustering high-dimensional datasets, November 2003, version 2.1.1Karypis, G., (2003) Cluto: A Clustering Toolkit, , University of Minnesota, Department of Computer Science, Minneapolis, MN 55455, November; Sanguinetti, G., Laidler, J., Lawrence, N.D., Automatic determination of the number of clusters using spectral algorithms (2005) International Workshop on Machine Learning for Signal Processing, pp. 55-60; Xu, X., Dbscan, , http://ifsc.ualr.edu/xwxu, Online, Available; Duin, R.P., Dutch handwritten numerals, , http://www.ph.tn.tudelft.nl/~duin; Hubert, L., Arabie, P., Comparing partitions (1985) Journal of Classification, 2 (1), pp. 193-218; Porter, M.F., An algorithm for suffix stripping (1980) Program, 14 (3), pp. 130-137; Hastie, T., Tibshirani, R., Friedman, J., (2001) The Elements of Statistical Learning, , Springer
Keywords: algorithm; Algorithms; article; artificial intelligence; automated pattern recognition; Cluster Analysis; Clustering; Clustering algorithms; computer assisted diagnosis; Distance measurement; Entropic subgraphs; entropy; Graph theory; Graphs; Hierarchical clustering; Hierarchical systems; Image enhancement; Image Interpretation, Computer-Assisted; Imaging, Three-Dimensional; methodology; Pattern Recognition, Automated; reproducibility; Reproducibility of Results; sensitivity and specificity; three dimensional imaging

Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states - Bernardes, J.; Gonçalves, H.; Ayres-de-Campos, D.; Rocha, A.P. (Early Human DevelopmentEarly Hum. Dev., 2008)
Background: A better understanding of gender influences on fetal heart rate can help to improve analysis of the latter and perhaps elucidate the increased risk of perinatal death that occurs in males. Aim: To assess differences in linear and complex heart rate dynamics according to fetal sex, in the antepartum period of normal term pregnancies, for patterns associated with fetal behavioural states. Study design and subjects: One hundred and eighty seven fetal heart rate segments of 10-minute duration, acquired with a system for computerized analysis of cardiotocograms and classified into fetal behavioural patterns A, B, C or D were analysed. They had been acquired from 24 female and 23 male term fetuses, with uneventful perinatal outcomes. Four different comparative studies between female and male fetuses were conducted, considering different adjustments for gestational age, weight and FHR pattern. Outcome measures: Indices of linear and nonlinear fetal heart rate variability, namely, long-term irregularity index, very low, low and high frequency spectral indices, approximate entropy and sample entropy. Results: Pattern B was the most frequent, both in female and male fetuses. Pattern A was more likely to be associated to female than male fetuses, whereas the opposite occurred with patterns C and D. Linear indices were significantly higher in male than in female fetuses, whereas the opposite occurred with nonlinear indices. Conclusions: Male fetuses exhibited significantly more linear and significantly less complex fetal heart rate activity than female fetuses, expressing signs of a more active autonomous nervous system and of less active complexity control systems. These aspects may need to be considered when interpreting FHR tracings. © 2007 Elsevier Ireland Ltd. All rights reserved.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: EHDEDdoi: 10.1016/j.earlhumdev.2007.12.001PubMed ID: 18248921Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina, Universidade do Porto and INEB (Instituto Nacional de Engenharia Biomédica), Porto, Portugal; email: jbernardes@mail.telepac.ptReferences: Ingemarsson, I., Herbst, A., Thorngren-Jerneck, K., Long term outcome after umbilical artery acidaemia at term birth: influence of gender and duration of fetal heart rate abnormalities (1997) Br J Obstet Gynaecol, 104 (10), pp. 1123-1127;Ingemarsson, I., Gender aspects of preterm birth (2003) BJOG, 110 (SUPPL. 20), pp. 34-38; DiPietro, J.A., Hodgson, D.M., Costigan, K.A., Hilton, S.C., Johnson, T.R., Development of fetal movement-fetal heart rate coupling from 20 weeks through term (1996) Early Hum Dev, 44 (2), pp. 139-151; DiPietro, J.A., Costigan, K.A., Shupe, A.K., Pressman, E.K., Johnson, T.R., Fetal neurobehavioral development: associations with socioeconomic class and fetal sex (1998) Dev Psychobiol, 33 (1), pp. 79-91; Ogueh, O., Steer, P., Gender does not affect fetal heart rate variation (1998) Br J Obstet Gynaecol, 105 (12), pp. 1312-1314; Dawes, N.W., Dawes, G.S., Moulden, M., Redman, C.W., Fetal heart rate patterns in term labor vary with sex, gestational age, epidural analgesia, and fetal weight (1999) Am J Obstet Gynecol, 180, pp. 181-187; Lange, S., Van Leeuwen, P., Geue, D., Hatzmann, W., Gronemeyer, D., Influence of gestational age, heart rate, gender and time of day on fetal heart rate variability (2005) Med Biol Eng Comput, 43 (4), pp. 481-486; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum Dev, 83 (9), pp. 585-591; Nijhuis, J.G., Prechtl, H.F., Martin Jr., C.B., Bots, R.S., Are there behavioural states in the human fetus? (1982) Early Hum Dev, 6 (2), pp. 177-195; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: the effect on linear and nonlinear parameters (2006) Physiol Meas, 27 (3), pp. 307-319; Goncalves, H., Rocha, A.P., Bernardes, J., Ayres-de-Campos, D., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med Biol Eng Comput, 44 (10), pp. 847-855; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, Pereira-Leite, L., SisPorto 2.0 - a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318.; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000, Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks, 3, pp. 637-641; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50, pp. 365-373; Task force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, Heart rate variability - standards of measurement, physiological interpretation and clinical use (1996) Circulation, 17, pp. 354-381; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grosssesse et de l'accouchement (2004) Encyclopédie Médico-Chirurgicale, 148 (5-49 -D-23), pp. 1-10; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci U. S. A., 88, pp. 2297-2301; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Fusheng, Y., Bo, H., Qingyu, T., Approximate entropy and its application in biosignal analysis (1998) Nonlinear biomedical signal processing - Volume II: Dynamical analysis and modelling, pp. 72-91. , Akay M. (Ed), IEEE Press; Pincus, S., Viscarello, R., Approximate entropy: a regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79, pp. 249-255; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press; Dudewicz, E., Mishra, S., (1998) Modern Mathematical Statistics, , John Wiley and Sons, Inc; Robles de Medina, P.G., Visser, G.H., Huizink, A.C., Buitelaar, J.K., Mulder, E.J., Fetal behaviour does not differ between boys and girls (2003) Early Hum Dev, 73 (1-2), pp. 17-26; Ryan, S.M., Goldberger, A.L., Pincus, S.M., Mietus, J., Lipsitz, L.A., Gender- and age-related differences in heart rate dynamics: are women more complex than men? (1994) J Am Coll Cardiol, 24 (7), pp. 1700-1707; Jensen-Urstad, K., Storck, N., Bouvier, F., Ericson, M., Lindblad, L.E., Jensen-Urstad, M., Heart rate variability in healthy subjects is related to age and gender (1997) Acta Physiol Scand, 160 (3), pp. 235-241; Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am J Physiol Heart Circ Physiol, 290 (6), pp. H2560-H2570; Kuo, T.B., Yang, C.C., Sexual dimorphism in the complexity of cardiac pacemaker activity (2002) Am J Physiol Heart Circ Physiol, 283 (4), pp. H1695-H1702; Groome, L.J., Mooney, D.M., Holland, S.B., Smith, L.A., Atterbury, J.L., Dykman, R.A., Behavioral state affects heart rate response to low-intensity sound in human fetuses (1999) Early Hum Dev, 54 (1), pp. 39-54; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin Sci (Lond), 92 (4), pp. 345-349; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, Suppl, 57 (1), pp. 33-37; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynecol, 106, pp. 1307-1310; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynaecol Obstet, 62 (2), pp. 141-147; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118 (1), pp. 52-60; Dawes, G.S., Moulden, M., Redman, C.W., Improvements in computerized fetal heart rate analysis antepartum (1996) J Perinat Med, 24 (1), pp. 25-36
Keywords: article; Behavior; Cardiotocography; comparative study; Computerized analysis; Entropy and spectral analysis; Female; Fetal behavioural states and sex; Fetal heart rate; Fetal monitoring; Fetal Movement; fetus; fetus heart rate; Gestational Age; heart hemodynamics; Heart Rate, Fetal; human; Humans; male; normal human; Pregnancy; Pregnancy Outcome; Sex Characteristics; sex difference; SisPorto

Linear and nonlinear heart-rate analysis in a rat model of acute anoxia - Gonçalves, H.; Henriques-Coelho, T.; Bernardes, J.; Rocha, A.P.; Nogueira, A.; Leite-Moreira, A. (Physiological MeasurementPhysiol. Meas., 2008)
The objective of this study was the assessment of heart-rate (HR) dynamics with linear and nonlinear methods during episodes of mechanical ventilation and acute anoxia in rats. Namely, to assess whether linear and nonlinear HR analysis was able to discriminate acute anoxia from baseline in rats and if this was consistent with human foetal and adult studies. Five HR segments of 1 min duration, during baseline recording, mechanical ventilation and first, second and third minutes of induced acute anoxia, were analysed in ten adult Wistar rats. Linear time and frequency domain and nonlinear methods were used, namely mean HR (mHR), long-term irregularity (LTI), interval index (II), low frequency (LF) and high frequency (HF), approximate entropy (ApEn) and sample entropy (SampEn). New parameters for the entropy indices are proposed for the analysis of rats' HR. Bootstrap percentile confidence intervals and nonparametric statistical tests were used in the evaluation of the differences between segments. During mechanical ventilation a clear spectral band was detectable at the ventilation rate, but mHR, II and the 'new' entropy indices were the only significantly changed indices. In the transition from baseline-mechanical- ventilation to mechanical-ventilation-induced anoxia, a statistically significant decrease of mHR, II and entropy indices was observed, clearly discriminating these two instances, whereas most linear indices increased. With continued anoxia, most linear indices decreased significantly, whereas entropy remained stably low. These results are consistent with other foetal human and non-human studies and evidence that the rat model may be used for further research on linear and nonlinear analysis of heart-rate dynamics. The transition from baseline to acute anoxia was encompassed by signs of increased activation of the autonomic nervous system sympathetic branch, and decreased or blunted activity of the HR complexity regulatory centres. © 2008 Institute of Physics and Engineering in Medicine.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: PMEAEdoi: 10.1088/0967-3334/29/9/010PubMed ID: 18784391Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade Do Porto, Rua do Campo Alegre 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptReferences: American College of Obstetricians and Gynecologists. ACOG Practice Bulletin. Clinical Management Guidelines for Obstetrician-Gynecologists, Number 70, December 2005 (2005) Obstet. Gynecol., 106, pp. 1453-1460;Ayres-De-Campos, D., Bernardes, J., Garrido, A., Marques-De-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Mat. Fet. Med., 9 (5), pp. 311-318; Ayres-De-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto® validation study (2005) Eur. J. Obstet. Gynecol. Reprod. Biol., 118 (1), pp. 52-60; Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am. J. Physiol. Heart Circ. Physiol., 290 (6), pp. 2560-H2570; Beckers, F., Verheyden, B., Ramaekers, D., Swinghedauw, B., Aubert, A.E., Effects of autonomic blockade on non-linear cardiovascular variability indices in rats (2006) Clin. Exp. Pharmacol. Physiol., 33 (5-6), pp. 431-439; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int. J. Gynecol. Obstet., 62 (2), pp. 141-147; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J. Perinat. Med., 19, pp. 61-65; Cerutti, C., Gustin, M.P., Paultre, C.Z., Lo, M., Julien, C., Vincent, M., Sassard, J., Autonomic nervous-system and cardiovascular variability in rats-a spectral-analysis approach (1991) Am. J. Physiol., 261, pp. 1292-H1299; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J. Matern. Fetal Invest., 8, pp. 23-26; Dudewicz, E., Mishra, S., (1988) Modern Mathematical Statistics; Felgueiras, C., Marques-De-Sá, J.P., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomedical Eng., 36, pp. 197-201; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-De-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Human Develop., 83 (9), pp. 585-591; Gonçalves, H., Rocha, A.P., Ayres-De-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol. Meas., 27 (3), pp. 307-319; Gonçalves, H., Rocha, A.P., Ayres-De-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med. Biol. Eng. Comput., 44 (10), pp. 847-855; Hayes, M., (1996) Statistical Digital Signal Processing and Modelling; Henriques-Coelho, T., Correia-Pinto, J., Roncon-Albuquerque, R., Baptista, M.J., Lourenco, A.P., Oliveira, S.M., Brandao-Nogueira, A., Leite-Moreira, A.F., Endogenous production of ghrelin and beneficial effects of its exogenous administration in monocrotaline-induced pulmonary hypertension (2004) Am. J. Physiol. Heart Circ. Physiol., 287 (6), pp. 2885-H2890; Kuwahara, M., Yayou, K., Ishii, K., Hashimoto, S., Tsubone, H., Sugano, S., Power spectral analysis of heart rate variability as a new method for assessing autonomic activity in the rat (1994) J. Electrocardiology, 27 (4), pp. 333-337; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur. J. Obstet. Gynecol. Reprod. Biol., 114 (2), pp. 137-143; Lourenço, A.P., Roncon-Albuquerque, R., Bras-Silva, C., Faria, B., Wieland, J., Henriques-Coelho, T., Correia-Pinto, J., Leite-Moreira, A.F., Myocardial dysfunction and neurohumoral activation without remodeling in left ventricle of monocrotaline-induced pulmonary hypertensive rats (2006) Am. J. Physiol. Heart Circ. Physiol., 291 (4), pp. 1587-H1594; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000: Proc. IEEE-INNS-ENNS Int. Joint Conf. on Neural Network, 3, pp. 637-641; Martinez, W.L., Martinez, A.R., (2002) Computational Statistics Handbook with MATLAB; Moraru, L., Cimponeriu, L., Tong, S., Thakor, N., Bezerianos, A., Characterization of heart rate variability changes following asphyxia in rats (2004) Methods Inf. Med., 43 (1), pp. 118-121; Moraru, L., Tong, S., Malhotra, A., Geocadin, R., Thakor, N., Bezerianos, A., Investigation of the effects of ischemic preconditioning on the HRV response to transient global ischemia using linear and nonlinear methods (2005) Med. Eng. Phys., 27 (6), pp. 465-473; Murasato, Y., Hirakawa, H., Harada, Y., Nakamura, T., Hayashida, Y., Effects of systemic hypoxia on R-r interval and blood pressure variabilities in conscious rats (1998) Am. J. Physiol., 275, pp. 797-H804; Niklasson, U., Wiklund, U., Bjerle, P., Olofsson, B.O., Heart-rate variation-what are we measuring? (1993) Clin. Physiol., 13 (1), pp. 71-79; Pincus, S., Aproximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Pincus, S.M., Gevers, E.F., Robinson, I.C.A.F., Vandenberg, G., Roelfsema, F., Hartman, M.L., Veldhuis, J.D., Females secrete growth hormone with more process irregularity than males in both humans and rats (1996) Am. J. Physiol., 270, pp. 107-E115; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet. Gynecol., 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am. J. Physiol. Heart Circ. Physiol., 278, pp. 2039-H2049; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans. Biomed. Eng., 50 (3), pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Valimaki, I.A., Rosen, K.G., Ekholm, E.M., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labour (2005) BJOG, 112 (4), pp. 418-423; Task force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, Heart rate variability-standards of measurement, physiological interpretation and clinical use (1996) Circulation, 93, pp. 1043-1065; Vieira, P., Marques-De-Sá, J.P., Bernardes, J., Fractal analysis of foetal heart rate (2004) Proc. Biosignal 2004, pp. 53-55
Keywords: acute disease; animal experiment; animal model; Animals; Anoxia; article; artificial ventilation; bootstrapping; controlled study; entropy; Female; Fetal monitoring; frequency analysis; Heart rate; Heart rate variability; Humans; Linear analysis; linear system; lung ventilation; Models, Cardiovascular; nonhuman; nonlinear system; priority journal; rat; Rats; Rats, Wistar; Rattus; Rattus norvegicus; Respiration, Artificial; Statistical analysis; Variability; Wistar rat; Wistar rats

A list scheduling algorithm for scheduling multi-user jobs on clusters - Barbosa, J.; Monteiro, A.P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper addresses the problem of scheduling multi-user jobs on clusters, both homogeneous and heterogeneous. A user job is composed by a set of dependent tasks and it is described by a direct acyclic graph (DAG). The aim is to maximize the resource usage by allowing a floating mapping of processors to a given job, instead of the common mapping approach that assigns a fixed set of processors to a user for a period of time. The simulation results show a better cluster usage. The scheduling algorithm minimizes the total length of the schedule (makespan) of a given set of parallel jobs, whose priorities are represented in a DAG. The algorithm is presented as producing static schedules although it can be adapted to a dynamic behavior as discussed in the paper. © 2008 Springer Berlin Heidelberg.
Conference code: 75089Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-92859-1_13Language of Original Document: EnglishCorrespondence Address: Barbosa, J.; Faculdade de Engenharia, Departamento de Engenharia Informática, Universidade Do Porto, Rua Dr. Roberto Frias, Porto 4200-465, Portugal; email: jbarbosa@fe.up.ptReferences: Amoura, A.K., Bampis, E., König, J.-C., Scheduling algorithms for parallel gaussian elimination with communication costs (1998) IEEE Transactions on Parallel and Distributed Systems, 9 (7), pp. 679-686;Barbosa, J., Morais, C., Nobrega, R., Monteiro, A.P., Static scheduling of dependent parallel tasks on heterogeneous clusters. In: Heteropar 2005 (2005) IEEE Computer Society, pp. 1-8. , Los Alamitos; Barbosa, J., Padilha, A.J., Algorithm-dependent method to determine the optimal number of computers in parallel virtual machines (1999) LNCS, 1573, pp. 508-521. , Hernández, V, Palma, J.M.L.M, Dongarra, J, eds, VECPAR 1998, Springer, Heidelberg; Barbosa, J., Tavares, J., Padilha, A.J., Linear algebra algorithms in a heterogeneous cluster of personal computers (2000) Proceedings of 9th Heterogeneous Computing Workshop, pp. 147-159. , IEEE CS Press, Los Alamitos; Berman, F., Wolski, R., Figueira, S., Schopf, J., Shao, G., Application-level scheduling on distributed heterogeneous networks (1996) Supercomputing 1996; Blazewicz, J., Dell'Olmo, P., Drozdowski, M., Maczka, P., Scheduling multiprocessor tasks on parallel processors with limited availability (2003) European journal of Operational Research, 149, pp. 377-389; Blazewicz, J., Machowiak, M., Weglarz, J., Kovalyov, M., Trystram, D., Scheduling malleable tasks on parallel processors to minimize the makespan (2004) Annals of Operations Research, 129, pp. 65-80; Shivle, S., Mapping of subtasks with multiple versions in a heterogeneous ad hoc grid environment (2004) Heteropar 2004. IEEE Computer Society, , Los Alamitos; Kim, J.-K., Dynamically mapping tasks with priorities and multiple deadlines in a heterogeneous environment (2007) Journal of Parallel and Distributed Computing, 67, pp. 154-169; Geijn, R., Watts, J., Summa: Scalable universal matrix multiplication algorithm (1995), Technical Report CS-95-286, University of Tennessee, KnoxvilleGerasoulis, A., Yang, T., On the granularity and clustering of directed acyclic task graphs (1993) IEEE Transactions on Parallel and Distributed Systems, 686-701. , June; Jansen, K., Scheduling malleable parallel tasks: An asymptotic fully polynomial time approximation scheme (2004) Algorithmica, 39, pp. 59-81; Kwok, Y., Ahmad, I., Static scheduling algorithms for allocating directed task graphs to multiprocessors (1999) ACM Computing Surveys, 31 (4), pp. 406-471; Kwok, Y., Ahmad, I., On multiprocessor task scheduling using efficient state space search approaches (2005) Journal of Parallel and Distributed Computing, 65, pp. 1515-1532; Lepère, R., Mounié, G., Trystram, D., An approximation algorithm for scheduling trees of malleable tasks (2002) European journal of Operational Research, 142, pp. 242-249; Oh-Heum, C.K.-Y., Scheduling parallel tasks with individual deadlines (1999) Theoretical Computer Science, 215, pp. 209-223; Park, G.-L., Performance evaluation of a list scheduling algorithm in distributed memory multiprocessor systems (2004) Future Generation Computer Systems, 20, pp. 249-256; Shirazi, B., Wang, M., Pathak, G., Analysis and evaluation of heuristic methods for static task scheduling (1990) Journal of Parallel and Distributing Computing, 10, pp. 222-232; Sinnen, O., Sousa, L., List scheduling: Extension for contention awareness and evaluation of node priorities for heterogeneous cluster architectures (2004) Parallel Computing, 30, pp. 81-101; Topcuoglu, H., Hariri, S., Wu, M.-Y., Performance-effective and low-complexity task scheduling for heterogeneous computing (2002) IEEE Transactions on Parallel and Distributed Systems, 13 (3), pp. 260-274; Trystram, D., Scheduling parallel applications using malleable tasks on clusters (2001) 15th International Conference on Parallel and Distributed Processing Symposium Sponsors: Pole de Competivite "Aerospace Valley"; European Centre for Research and Advanced Training in ENSEEIHT; Institut National Polytechmique de Toulouse; Institut de Recherche en Informatique de Toulouse; Universidade do Porto; Universite Paul Sabatier
Keywords: Cluster computing; Dynamic behaviors; Electric load shedding; High performance liquid chromatography; List scheduling; Paper addresses; Parallel algorithms; Parallel task; Resource usage; Scheduling; Scheduling algorithms; Simulation results; Static and dynamic scheduling; Total length

Microstructure, mechanical properties and chemical degradation of brazed AISI 316 stainless steel/alumina systems - Paiva, O.C.; Barbosa, M.A. (Materials Science and Engineering AMater. Sci. Eng. A, 2008)
The main aims of the present study are simultaneously to relate the brazing parameters with: (i) the correspondent interfacial microstructure, (ii) the resultant mechanical properties and (iii) the electrochemical degradation behaviour of AISI 316 stainless steel/alumina brazed joints. Filler metals on such as Ag-26.5Cu-3Ti and Ag-34.5Cu-1.5Ti were used to produce the joints. Three different brazing temperatures (850, 900 and 950 °C), keeping a constant holding time of 20 min, were tested. The objective was to understand the influence of the brazing temperature on the final microstructure and properties of the joints. The mechanical properties of the metal/ceramic (M/C) joints were assessed from bond strength tests carried out using a shear solicitation loading scheme. The fracture surfaces were studied both morphologically and structurally using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction analysis (XRD). The degradation behaviour of the M/C joints was assessed by means of electrochemical techniques. It was found that using a Ag-26.5Cu-3Ti brazing alloy and a brazing temperature of 850 °C, produces the best results in terms of bond strength, 234 ± 18 MPa. The mechanical properties obtained could be explained on the basis of the different compounds identified on the fracture surfaces by XRD. On the other hand, the use of the Ag-34.5Cu-1.5Ti brazing alloy and a brazing temperature of 850 °C produces the best results in terms of corrosion rates (lower corrosion current density), 0.76 ± 0.21 μA cm
Cited By (since 1996): 11Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.msea.2007.07.015Language of Original Document: EnglishCorrespondence Address: Paiva, O.C.; Instituto Superior de Engenharia do Porto (ISEP), Rua Dr. Antonio Bernardino Almeida 431, 4200-072 Porto, Portugal; email: omp@isep.ipp.ptReferences: Schwartz, M.M., (1990) Ceramic Joining, pp. 75-140. , Schwartz M.M. (Ed), ASM International, Ohio;Nicholas, M.G., (1986) Br. Ceram. Trans. J., 85, pp. 144-146; Loehamn, R.E., Tomsia, A.P., (1992) Acta Metall. Mater., 40, pp. S75-S83; Hao, H., Wang, Y., Jin, Z., Wang, X., (1995) J. Mater. Sci., 30, pp. 4107-4111; Hao, H., Wang, Y., Jin, Z., Wang, X., (1995) J. Mater. Sci., 30, pp. 1233-1239; Rongti, L., Wei, P., Jian, C., Jie, L., (2002) Mater. Sci. Eng. A, 335, pp. 21-25; Paiva, O.C., Barbosa, M.A., (1997) J. Mater. Sci., 32, pp. 653-659; Paiva, O.C., Barbosa, M.A., (1995) Advances in Materials Science and Implant Orthopaedic Surgery, pp. 275-290. , Kossowsky R., and Kossovsky N. (Eds), Kluwer Academic Publishers, Dordrecht, The Netherlands; Paiva, O.C., Barbosa, M.A., (2000) J. Mater. Sci., 35, pp. 1165-1175; Rocha, L.A., Barbosa, M.A., Puers, R., (1985) J. Mater Sci.: Mat. Med., 6, pp. 835-838; Paiva, O.C., Ferreira, L., Barbosa, M.A., (1998) Interfacial Science in Ceramic Joining, NATO/ARW Series (3. High Technology), 53, pp. 329-340. , Bellosi A., Kosmac e T., and Tomsia A.P. (Eds), Kluwer Academic Press, Dordrecht, The Netherlands; Ariza, E., Rocha, L.A., Paiva, O.C., (2004) Eurocorr2004 Conference Proceedings, , Nice, France CD-Rom; Idrissi, H., Audisio, S., Elmouaffek, S., Chastrette, M., (1987) Materiaux et Techniques, pp. 433-437; Idrissi, H., Millet, J.P., Audisio, S., Irhzo, A., (1994) J. Mater. Sci., 29, pp. 5327-5332; Niu, Y., Gesmundo, F., Viani, F., Wu, W., (1997) Oxidat. Met., 47, pp. 21-52; Stern, M., Geary, A.L., (1957) Corrosion, 13, pp. 139-143; Saiz, E., Cannon, R.M., Tomsia, A.P., (2000) Acta Mater., 48, pp. 4449-4462; Kang, S., (1989) Ceram. Bull., 68, pp. 1608-1617; Elssner, G., Petzow, G., (1990) ISIJ Int., 30, pp. 1011-1032; Kim, D.H., Wang, S.H., Chun, S.S., (1991) J. Mater. Sci., 26, pp. 3223-3234; Meier, A., Javernick, D.A., Edwards, G.R., (1999) JOM, pp. 44-47; Zhai, Y., North, T.H., Ren, J., (1997) J. Mater. Sci., 32, pp. 1399-1404; W. Weise, W. Malikowski, W. Bohm, Degussa AG, Hanau, Germany, Internal Report (1995)Moret, F., Eustathopoulos, N., (1993) Journal de Physique IV, Colloque, C7 (3), pp. 1043-1052; Gibbesch, B., Elssener, G., Petzow, G., (1992) Biomaterials, 13 (7), pp. 455-461; (1992) Joint Committee on Powder Diffraction Standards, Powder Diffraction File, , ASTM, Philadelphia, PA; Lee, W.C., Kwon, O.Y., Kang, C.S., (1995) J. Mater. Sci., 30, pp. 1679-1688; Shreir, L.L., (1978) Corrosion-Metal/Environment Reactions. 2nd ed., 1, pp. 3:31-3:63. , Shreir L.L. (Ed), Newnes-Butterworths; A.D. Bernache, in: M.A. Barbosa et al. (Ed.), Biomaterials Degradation. Fundamental aspects and related clinical phenomena, Elsevier, Amsterdam, E-MRS Monographs I, 1991, 111-167Sequeira, C.A.C., (1995) Br. Corros. J., 30, pp. 137-140; LaQue, F.L., (1975) Marine Corrosion, p. 179. , LaQue F.L. (Ed), John Wiley & Sons; Paiva, O.C., Barbosa, M.A., (1998) Bioceramics 11, pp. 699-702. , LeGeros R.Z., and LeGeros J. (Eds), World Scientific Publishing Co. Pte. Ltd., Singapore; Paiva, O.C., Barbosa, M.A., (1999) Bioceramics 12, pp. 95-98. , Ohgushi H., Hastings G.W., and Yoshikawa T. (Eds), World Scientific Publishing Co. Pte. Ltd., Singapore; Walkiden, G.W., (1978) Corrosion-Metal/Environment Reactions. 2nd ed., 1, pp. 6:1-6:23. , Shreir L.L. (Ed), Newnes-Butterworths; Janssens, S., Rocha, L.A., Bosschaerts, L., Barbosa, M.A., Puers, R., Villé, H., Geers, R., (1996) Prev. Vet. Med., 25, pp. 249-258; Tsalev, D.L., Zaprianov, Z.K., (1983) Atomic Absorption Spectrometry in Occupational and Environmental Health Practice, , CRC Press, Boca Raton pp. 189-192
Keywords: Active metal brazing; Alumina; Bond strength (materials); Brazing; Electrochemical degradation; Filler metals; fracture; Interface composition; Metal/ceramic joining; Metallic matrix composites; morphology; Processing parameters; Shear strength; Stainless steel

Minimizing the imbalance problem in chromatographic profile classification with one-class classifiers - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper presents a new classification approach to deal with class imbalance in TLC patterns, which is due to the huge difference between the number of normal and pathological cases as a consequence of the rarity of LSD diseases. The proposed architecture is formed by two decision stages: the first is implemented by a one-class classifier aiming at recognizing most of the normal samples; the second stage is a hierarchical classifier which deals with the remaining outliers that are expected to contain the pathological cases and a small percentage of normal samples. We have also evaluated this architecture by a forest of classifiers, using the majority voting as a rule to generate the final classification. The results that were obtained proved that this approach is able to overcome some of the difficulties associated with class imbalance. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_41Language of Original Document: EnglishCorrespondence Address: Sousa, A. V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Keir, G., Winchester, B.G., Clayton, P., Carbohydrate-deficient Glycoprotein Syndromes: Inborn Errors of Protein Glycosylate (1999) Ann. Clin. Biochem, 36 (PART 1), pp. 20-36;Durand, G., Seta, N., Protein Glycosylation and Diseases: Blood and Urinary Oligosaccharides as Markers for Diagnosis and Therapeutic Monitoring (2000) Clin. Chem, 46, pp. 795-805; Scriver, S.R., Beaudet, A.L., Sly, W.S., Valle, D., (2001) The Metabolic Bases of Inherited Disease, 3. , MCGraw-Hill, New-York; Friedman, R.B., Williams, M.A., Moser, H.W., Kolodny, E.H., Improved Thin-Layer Chromatographic Method in the Diagnosis of Mannosidosis (1978) Clinical Chemistry, 24, pp. 1576-1577; Kurczynski, T.W., Kendzierski, K.S., Sewell, A.C., Kuczynski, T.W., Urinary Oligosaccharides in Pregnant or Lactating Women: Pitfall in Screening (1993) Clin. Chem, 39, pp. 2346-2347; Sewell, A.C., Urinary Oligosaccharides. Techniques in Diagnostic Human (1991) Biochemical Genetics, 219-231; Duvdevani-Bar, S., Edelman, S., Visual Recognition and Categorization on the Basis of Similarities to Multiple Class Prototypes (1999) Int. J. Comput. Vision, 33, pp. 201-228; Pekalska, E., Duin, R.P.W., Dissimilarity Representations Allow for Building Good Classifiers (2002) Pattern Recogn. Lett, 23, pp. 943-956; Goldstone, R.L., Son, J.Y., Similarity (2005) Cambridge Handbook of Thinking and Reasoning, pp. 13-36. , Holyoak, K, Morrison, R, eds, Cambridge University Press, Cambridge; Pekalska, E., Duin, R.P.W., (2005) The Dissimilarity Representation for Pattern Recognition -Fundations and Applications, 64. , World Scientific Publishing, Singapore; Lavine, B.K., Clustering and Classification of Analytical Data (2000) Encyclopedia of Analytical Chemistry: Instrumentation and Applications, pp. 9689-9710. , Meyers, R.A, ed, John Wiley & Sons, Chichester; Kubat, M., Holte, R., Matwin, S.: Learning when Negative Examples Abound. In: van Someren, M., Widmer, G. (eds.) ECML 1997. LNCS, 1224, pp. 146-153. Springer, Heidelberg (1997)Skurichina, M., Raudys, S., Duin, R.P.W., K-Nearest Neighbors Directed Noise Injection in Multilayer Perceptron Training (2000) IEEE Transactions on Neural Networks, 11; Chawla, N.V., Japkowicz, N., Kolcz, A., Editorial: Special Issue: Learning from Imbalanced Data Sets (2004) Sigkdd Explorations, 6, pp. 1-6; Tax, D.M.J., (2001) One-class Classification; Concept-learning in the Absence of Counter-examples, , Ph.D. thesis: Delft University of Technology; Sousa, A.V., Mendonça, A.M., Campilho, A., Chromatographic Pattern Classification (2007) IEEE Trans. on Biomedical Engineering, , doi:10.1109/TBME.2008.919852; Paclik, P., Duin, R.P.W., Dissimilarity-based Classification of Spectra: Computational Issues (2003) Real-Time Imaging, 9, pp. 237-244; Paclik, P., Duin, R.P.W., Classifying Spectral Data using Relational Representation (2003) Proc. of Spectral Imaging Workshop, , Graz, Austria; Sousa, A.V., Mendonça, A.M., Campilho, A., Dissimilarity-based Classification of Chromatographic Profiles (2007) Pattern Analysis and Applications, , doi:10.1007/sl0044-008-0113-2; Pekalska, E., Paclik, P., Duin, R.P.W., A Generalized Kernel Approach to Dissimilarity-based Classifcation (2001) Journal of Machine Learning Research, 2, pp. 175-211; Ripley, B.D., (2004) Pattern Recognition and Neural Networks, , Cambridge University Press, Cambridge; Visa, S., Ralescu, A., Learning Imbalanced and Overlapping Classes Using Fuzzy Sets (2003) Workshop on Learning from Imbalanced Datasets II, ICML, , Washington DC
Keywords: Class imbalances; Classification (of information); Classification approach; Classifiers; Heidelberg (CO); Hierarchical classifiers; Image analysis; Imaging techniques; Imbalance problems; International conferences; Learning systems; Majority voting; Pathological cases

Molecular epidemiology of pseudomonas aeruginosa clinical isolates from Portuguese Central Hospital - Fonseca, A.P.; Correia, P.; Extremina, C.I.; Sousa, J.C.; Tenreiro, R.; Barros, H. (Folia MicrobiologicaFolia Microbiol., 2008)
The relatedness between clinical isolates of P. aeruginosa obtained from patients during their stay in a Portuguese Central Hospital was evaluated. Genotypic fingerprinting (M13-PCR), phenotypic methods (biotyping and antibiotyping) and epidemiological information (spatial and temporal links) were used to evaluate the relatedness between 88 clinical isolates (68 patients), selected randomly out of 189. Sixty-two M13 types were found, 12 of them containing isolates from more than one patient. Thirty-four antibiotypes were found, as well as a significant association (p < 0.05) between epidemic isolates and multiresistance patterns. The nosocomial transmission of P. aeruginosa strains may be limited since M13 typing demonstrated a high degree of diversity among all the isolates, suggesting the occurrence of mainly independent infectious episodes. The results show the possible occurrence of cross-acquisition, cross-colonization and cross-infection and suggest an epidemic population structure for P. aeruginosa in this hospital.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: FOMIAdoi: 10.1007/s12223-008-0086-yLanguage of Original Document: EnglishCorrespondence Address: Fonseca, A. P.Rua Roberto Frias s/n, 4200-465 Porto, Portugal; email: apfonseca08@sapo.ptChemicals/CAS: DNA, BacterialReferences: Bergmans, D., Bonten, M., van tiel, F., Gaillard, C., London, N., van der Geest, S., de Leeuw, P., Stobbrringh, E., Value of phenotyping methods as an initial screening of Pseudomonas aeruginosa in epidemiologic studies (1997) Infection, 25, pp. 350-354;Bertrand, X., Thouverez, M., Talon, D., Boillot, A., Capellier, G., Floriot, C., Helias, J.P., Endemicity, molecular diversity and colonization routes of Pseudomonas aeruginosa in intensive care units (2001) Intens.Care Med., 27, pp. 1263-1268; Brízio, A., Silva, A., Canas, E., Ferreira, T., Lito, L.M., Cristino, J.M., Salgado, M.J., Duarte, A., Spread of ln58 containing bla VIM-2 among Pseudomonas aeruginosa (2006) Clin.Microbiol.Infect.Dis., 12 (SUPPL. 4), p. 931; Brízio, A., Vasco, S., Gonçalves, A.R., Lito, L.M., Cristino, J.M., Salgado, M.J., Duarte, A., Survey of extended-spectrum β-lactamases in Escherichia coli isolates from a Portuguese hospital and characterisation of a novel class 1 integron (In60A) carrying the blaCTX-M-9 gene (2006) Internat.J.Antimicrob.Agents, 28, pp. 320-324; Buchholz, P., Richter, M., Fiedler, G., Halle, E., Epidemiological fingerprinting of multiresistant strains of Pseudomonas aeruginosa isolated from patients of intensive care units of the Charité Hospital, Berlin (1995) Med.Microbiol.Lett., 4, pp. 7-13; Černohorská, L., Votava, M., Antibiotic synergy against biofilm-forming Pseudomonas aeruginosa (2008) Folia Microbiol, 53, pp. 57-61; Elaichouni, A., Verschraegen, G., Claeys, G., Devleeschouwer, M., Godard, C., Vaneechoutte, M., Pseudomonas aeruginosa serotype O12 outbreak studied by arbitrary primer PCR (1994) J.Clin.Microbiol., 32, pp. 666-671; Fonseca, A.P., Correia, P., Fonseca, A.F., Tenreiro, R., Sousa, J.C., Polyphasic approach to the characterization of Pseudomonas aeruginosa isolates from a Portuguese Central Hospital (2004) Clin.Microbiol.Infect., 10 (SUPPL. 3), p. 1113; Fonseca, A.P., Correia, P., Sousa, J.C., Tenreiro, R., Association patterns of Pseudomonas aeruginosa clinical isolates as revealed by virulence traits, antibiotic resistance, serotype and genotype (2007) FEMS Immunol.Med.Microbiol., 51, pp. 505-516; Grundmann, H., Kropec, A., Hartung, D., Berner, R., Daschner, F., Pseudomonas aeruginosa in a neonatal intensive care unit: Reservoirs and ecology of the nosocomial pathogen (1993) J.Infect.Dis., 168, pp. 943-947; Grundmann, H.J., Towner, K.J., Dijkshoorn, L., Gerner-smidt, P., Maher, M., Seifert, H., Vaneechoutte, M., Multicenter study using standardized protocols and reagents for evaluation of reproducibility of PCR-based fingerprinting of Acinetobacter spp (1997) J.Clin.Microbiol., 35, pp. 3071-3077; Hoštacká, A., Čižnár, I., Slobodníková, L., Kotulová, D., Clinical Pseudomonas aeruginosa: Potential factors of pathogenicity and resistance to antimicrobials (2006) Folia Microbiol, 51, pp. 633-638; Hunter, P.R., Gaston, M.M., Numerical index of the discriminatory ability of typing systems: An application of Simpson's index of diversity (1989) J.Clin.Microbiol., 26, pp. 2465-2466; Huston, W.M., Potter, A.J., Jennings, M.P., Rello, J., Hauser, A.R., McEwan, A.G., Survey of ferroxidase expression and siderophore production in clinical isolates of Pseudomonas aeruginosa (2004) J.Clin.Microbiol., 42, pp. 2806-2809; Jalaluddin, S., Devaster, J.-M., Scheen, R., Gerard, M., Butzler, J.-P., Molecular epidemiological study of nosocomial Enterobacter aerogenes isolates in a Belgian hospital (1998) J.Clin.Microbiol., 36, pp. 1846-1852; Juretschko, S., Labombardi, V.J., Lerner, S.A., Schreckenberger, P.C., Pseudomonas AST Study Group: Accuracies of β-lactam susceptibility test results for Pseudomonas aeruginosa with four automated systems (BD Phoenix, MicroScan WalkAway, Vitek, and Vitek 2) (2007) J.Clin.Microbiol., 45, pp. 1339-1342; King, E.O., Ward, M.K., Raney, D.E., Two simple media for the demonstration of pyocyanin and fluorescein (1954) J.Lab.Clin.Med., 44, pp. 301-307; Kiska, D.L., Gilligan, P.H., Pseudomonas and Burkholderia (1999) Manual of Clinical Microbiology, pp. 517-525. , in P.R.Murray,E.J.Baron,M.A.Pfaller,F.C.Tenover,R.H.Yolken(Eds) 7th ed. American Society for Microbiology,Washington (DC); Morales, G., Wiehlmann, L., Gudowius, P., van Delden, C., Tümmler, B., Martínez, J.L., Rojo, F., Structure of Pseudomonas aeruginosa populations analyzed by single nucleotide polymorphism and pulsed-field gel electrophoresis genotyping (2004) J.Bacteriol., 186, pp. 4228-4237; Nogueira, J.A., (1995) Pseudomonas Aeruginosa - Agente Nosocomial, , (In Portuguese) PhD Thesis. Faculdade de Medicina, Universidade do Porto, Porto (Portugal); Olive, P.B.D., Principles and applications of methods for DNA-based typing of microbial organisms (1999) J.Clin.Microbiol., 37, pp. 1661-1669; Pirnay, J.P., de Vos, D., Cochez, C., Bilocq, F., Vanderkelen, A., Zizi, M., Ghysels, B., Cornelis, P., Pseudomonas aeruginosa displays an epidemic population structure (2002) Environ.Microbiol., 4, pp. 898-911; Pirnay, J.P., Matthijs, S., Colak, H., Chablain, P., Bilocq, F., Van eldere, J., de Vos, D., Cornelis, P., Global Pseudomonas aeruginosa biodiversity as reflected in a Belgian river (2005) Environ.Microbiol., 7, pp. 969-980; Speijer, H., Savelkoulp, P.H.M., Bonten, M.J., Stobberingh, E.E., Tjhie, J.H.T., Application of different genotyping methods for Pseudomonas aeruginosa in a setting of endemicity in an intensive care unit (1999) J.Clin.Microbiol., 37, pp. 3654-3661; Tenover, F., Arbeit, R.D., Goering, R.V., Mickelsen, P.A., Murray, B.E., Persing, D.H., Swaminathan, B., Interpreting chromosomal DNA restriction patterns produced by pulsed-field gel electrophoresis: Criteria for bacterial strain typing (1995) J.Clin. Microbiol., 33, pp. 2233-2239; Wiehlmann, L., Wagner, G., Cramer, N., Siebert, B., Gudowius, P., Morales, G., Köhler, T., Tümmler, B., Population structure of Pseudomonas aeruginosa (2007) Proc.Nat.Acad.Sci.USA, 104, pp. 8101-8106
Keywords: antibiotic resistance; article; bacterial DNA; cross infection; disease transmission; DNA, Bacterial; Drug Resistance, Microbial; Electrophoresis, Gel, Pulsed-Field; epidemiology; genetics; genotype; Hospitals, Teaching; human; Humans; isolation and purification; microbiology; polymerase chain reaction; Portugal; Pseudomonas aeruginosa; Pseudomonas infection; Pseudomonas Infections; pulsed field gel electrophoresis; Sampling Studies; statistics; teaching hospital

Nanocrystalline diamond as a coating for joint implants: Cytotoxicity and biocompatibility assessment - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Journal of NanomaterialsJ. Nanomater., 2008)
Nanocrystalline diamond (NCD) coatings combine a very low surface roughness with the outstanding diamond properties, such as superlative hardness, low self-friction coefficient, high wear and corrosion resistance, and biotolerance, which are ideal features for applications in medicine (knee and hip replacement) and surgical tools. The present work presents a comprehensive study of the cytotoxicity and biocompatibility of NCD films grown by hot-filament chemical vapour deposition (HFCVD) technique, aiming such future applications. Cytotoxicity was evaluated in vitro by seeding human gingival fibroblasts on the NCD surface for 14 days, while specific biocompatibility was assessed on samples seeded with human bone marrow-derived osteoblasts during 21 days. The NCD coatings proved to be noncytotoxic in the preliminary human gingival fibroblast cell cultures, as denoted by a notable sequence of cell attachment, spreading, and proliferation events. In the specific biocompatibility assay envisaging bone tissue applications, NCD coatings induced human osteoblast proliferation and the stimulation of differentiation markers, compared to standard polystyrene tissue culture plates. Copyright © 2008.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusArt. No.: 894352doi: 10.1155/2008/894352Language of Original Document: EnglishCorrespondence Address: Silva, R. F.; Departamento de Engenharia Cerâmica e Vidro, Centro de Investigação em Materiais Cerâmicos e Compósitos (CICECO), Universidade de Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@ua.ptReferences: Grabarczyk, J., Batory, D., Louda, P., Couvrat, P., Kotela, I., Bakowicz Mitura, K., Carbon coatings for medical implants (2007) Journal of Achievements in Materials and Manufacturing Engineering, 20 (20), pp. 107-110;Jakubowski, W., Bartosz, G., Niedzielski, P., Szymanski, W., Walkowiak, B., Nanocrystalline diamond surface is resistant to bacterial colonization (2004) Diamond and Related Materials, 13 (10), pp. 1761-1763; Amaral, M., Abreu, C.S., Oliveira, F.J., Gomes, J.R., Silva, R.F., Biotribological performance of NCD coated Si3N4 -bioglass composites (2007) Diamond and Related Materials, 16, pp. 790-795; Amaral, M., Abreu, C.S., Oliveira, F.J., Gomes, J.R., Silva, R.F., Tribological characterization of NCD in physiological fluids (2008) Diamond and Related Materials, 17 (4-5), pp. 848-852; Nordsletten, L., Hgsen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: In vitro studies of new prosthesis coatings (1996) Biomaterials, 17 (15), pp. 1521-1527; Aspenberg, P., Anttila, A., Konttinen, Y.T., Benign response to particles of diamond and SiC: Bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17 (8), pp. 807-812; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour-deposited diamond (1995) Biomaterials, 16 (6), pp. 483-488; Bakowicz-Mitura, K., Bartosz, G., Mitura, S., Influence of diamond powder particles on human gene expression (2007) Surface Coatings Technology, 201 (13), pp. 6131-6135; Kulisch, W., Popov, C., Bliznakov, S., Surface and bioproperties of nanocrystalline diamond/amorphous carbon nanocomposite films (2007) Thin Solid Films, 515 (23), pp. 8407-8411; Popov, C., Kulisch, W., Reithmaier, J.P., Bioproperties of nanocrystalline diamond/amorphous carbon composite films (2007) Diamond and Related Materials, 16, pp. 735-739; Rubio-Retama, J., Hernando, J., Lpez-Ruiz, B., Synthetic nanocrystalline diamond as a third-generation biosensor support (2006) Langmuir, 22 (13), pp. 5837-5842; Siew, P.S., Loh, K.P., Poh, W.C., Zhang, H., Biosensing properties of nanocrystalline diamond film grown on polycrystalline diamond electrodes (2005) Diamond and Related Materials, 14, pp. 426-431; Wenmackers, S., Christiaens, P., Daenen, M., DNA attachment to nanocrystalline diamond films (2005) Physica Status Solidi (A), 202 (11), pp. 2212-2216; Yang, W., Hamers, R.J., Fabrication and characterization of a biologically sensitive field-effect transistor using a nanocrystalline diamond thin film (2004) Applied Physics Letters, 85 (16), pp. 3626-3628; Steinmller-Nethl, D., Kloss, F.R., Najam-Ul-Haq, M., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27 (26), pp. 4547-4556; Williams, D., Revisiting the definition of biocompatibility (2003) Medical Device Technology, 14 (8), pp. 10-13; Kue, R., Sohrabi, A., Nagle, D., Frondoza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like MG63 cells on silicon nitride ceramic discs (1999) Biomaterials, 20 (13), pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clinical Orthopaedics and Related Research, (244), pp. 296-301; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3 N 4 -bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23 (24), pp. 4897-4906; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond and Related Materials, 12, pp. 733-737; Amaral, M., Fernandes, A.J.S., Vila, M., Oliveira, F.J., Silva, R.F., Growth rate improvements in the hot-filament CVD deposition of nanocrystalline diamond (2006) Diamond and Related Materials, 15 (11-12), pp. 1822-1827; Almeida, F.A., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Silva, R.F., Nano to micrometric HFCVD diamond adhesion strength to Si3N4 (2007) Vacuum, 81 (11-12), pp. 1443-1447; Trigo Cabral, M.C., Costa, M.A., Fernandes, M.H., In vitro models of periodontal cells: A comparative study of long-term gingival, periodontal ligament and alveolar bone cell cultures in the presence of -glycerophosphate and dexamethasone (2007) Journal of Materials Science, 18 (6), pp. 1079-1088; Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testingpart I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in -MEM and in DMEM (2000) Biomaterials, 21 (11), pp. 1087-1094; Alberts, B., Johnson, A., Lewis, J., Ratt, M., Roberts, K., Walter, P., The cytoskeleton (2002) Molecular Biology of the Cell, , 4th New York, NY, USA Garland Science; Fawcett, D.W., Connective tissue (1994) A Textbook of Histology, pp. 133-169. , 12th New York, NY, USA Chapman Hall; Freshney, R.I., Biology of cultured cells (2000) Culture of Animal Cells: A Manual of Basic Technique, pp. 9-18. , 4th New York, NY, USA Wiley-Liss; Biological evaluation of medical devicespart 5: Tests for in vitro cytotoxicity, , International Organization for Standardization, Geneva, Switzerland, 1992; Okrj, W., Kamiska, M., Klimek, L., Szymaski, W., Walkowiak, B., Blood platelets in contact with nanocrystalline diamond surfaces (2006) Diamond and Related Materials, 15 (10), pp. 1535-1539; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494 (1-2), pp. 92-97; Kalbacova, M., Kalbac, M., Dunsch, L., The effect of SWCNT and nano-diamond films on human osteoblast cells (2007) Physica Status Solidi (B), 244 (11), pp. 4356-4359; Chong, K.F., Loh, K.P., Vedula, S.R.K., Cell adhesion properties on-photochemically functionalized diamond (2007) Langmuir, 23 (10), pp. 5615-5621; Bajaj, P., Akin, D., Gupta, A., Ultrananocrystalline diamond film as an optimal cell interface for biomedical applications (2007) Biomedical Microdevices, 9 (6), pp. 787-794; Stein, G.S., Lian, J.B., Molecular mechanisms mediating proliferation/differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocrine Reviews, 14 (4), pp. 424-442; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testingpart II: Effect of ascorbic acid, -glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21 (11), pp. 1095-1102; Sikavitsas, V.I., Temenoff, J.S., Mikos, A.G., Biomaterials and bone mechanotransduction (2001) Biomaterials, 22 (19), pp. 2581-2593; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21 (17), pp. 1803-1810; Webster, T.J., Smith, T.A., Increased osteoblast function on PLGA composites containing nanophase titania (2005) Journal of Biomedical Materials Research Part A, 74 (4), pp. 677-686; Kay, S., Thapa, A., Haberstroh, K.M., Webster, T.J., Nanostructured polymer/nanophase ceramic composites enhance osteoblast and chondrocyte adhesion (2002) Tissue Engineering, 8 (5), pp. 753-761; Balasundaram, G., Sato, M., Webster, T.J., Using hydroxyapatite nanoparticles and decreased crystallinity to promote osteoblast adhesion similar to functionalizing with RGD (2006) Biomaterials, 27 (14), pp. 2798-2805; Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Simon, S.P., Form and function of bone (1994) Orthopedic Basic Science, pp. 127-185. , Columbus, Ohio, USA American Academy of Orthopedic Surgeons; Palin, E., Liu, H., Webster, T.J., Mimicking the nanofeatures of bone increases bone-forming cell adhesion and proliferation (2005) Nanotechnology, 16 (9), pp. 1828-1835; Siegel, R.W., Creating nanophase materials (1996) Scientific American Magazine, 275 (6), pp. 74-79; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) Journal of Biomedical Materials Research, 51 (3), pp. 475-483; Webster, T.J., Schadler, L.S., Siegel, R.W., Bizios, R., Mechanisms of enhanced osteoblast adhesion on nanophase alumina involve vitronectin (2001) Tissue Engineering, 7 (3), pp. 291-301

Nanocrystalline diamond: In vitro biocompatibility assessment by MG63 and human bone marrow cells cultures - Amaral, M.; Dias, A.G.; Gomes, P.S.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
Nanocrystalline diamond (NCD) has a great potential for prosthetic implants coating. Nevertheless, its biocompatibility still has to be better understood. To do so, we employed several materials characterization techniques (SEM, AFM, micro-Raman spectroscopy) and cell culture assays using MG63 osteoblast-like and human bone marrow cells. Biochemical routines (MTT assays, Lowry's method, ALP activity) supported by SEM and confocal microscopy characterization were carried out. We used silicon nitride (Si 3N 4) substrates for NCD coatings based on a previous demonstration of the superior adhesion and tribological performance of these NCD coated ceramics. Results demonstrate an improved human osteoblast proliferation and the stimulation of differentiated markers, like ALP activity and matrix mineralization, compared with standard polystyrene tissue culture plates. The nanometric featuring of NCD, associated to its chemical affinity are key points for bone regeneration purposes. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31742PubMed ID: 18085649Language of Original Document: EnglishCorrespondence Address: Silva, R. F.; CICECO, Department of Ceramics and Glass Engineering, University of Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@cv.ua.ptChemicals/CAS: diamond, 7782-40-3; polystyrene, 9003-53-6; silicon nitride, 12033-89-5; Alkaline Phosphatase, EC 3.1.3.1; Ceramics; Coated Materials, Biocompatible; Diamond, 7782-40-3; Silicon Compounds; silicon nitride, 12033-89-5References: Ratner, B.D., Hoffman, A.S., Schoen, A.S., Lemons, J.E., (1996) Biomaterials Science: An Introduction to Materials in Medicine, , New York: Academic Press;;Emery, D.F.G., Clarke, H.J., Grover, M.L., Stanmore total hip replacement in younger patients: Review of a group of patients under 50 years of age at operation (1997) J Bone Joint Surg, 79, pp. 240-246; Shane, A.C., Monique, C., Yogesh, K.V., Erick, M.S., Michelle, D.M., David Moore, K., Surface crystalline phases and nanoindentation hardness of explanted zirconia femoral heads (2003) J Mater Sci: Mater Med, 14, pp. 863-867; Shane, A.C., Marc, D.F., Yogesh, K.V., William, R.L., Jack, E.L., Shanna, W., Ramakrishna, V., Nanostructured ceramics for biomedical implants (2002) J Nanosci Nanotechnol, 2, pp. 293-312; Palin, E., Liu, H., Webster, T.J., Mimicking the nanofeatures of bone increases bone-forming cell adhesion and proliferation (2005) Nanotechnology, 16, pp. 1828-1835; Webster, T.J., Siegel, R.W., Bizios, R., Osteoblast adhesion on nanophase ceramics (1999) Biomaterials, 20, pp. 1221-1227; Price, R.L., Haberstroh, K.M., Webster, T.J., Enhanced functions of osteoblasts on nanostructured surfaces of carbon and alumina (2003) Med Biol Eng Comput, 41, pp. 372-375; Perla, V., Webster, T.J., Better osteoblast adhesion on nanoparticulate selenium - A promising orthopedic implant material (2005) J Biomed Mater Res, 75 A, pp. 356-364; Fries, M.D., Vohra, Y.K., Nanostructure diamond film deposition on curved surfaces of metallic temporomandibular joint implant (2002) J Phys D: Appl Phys, 35, pp. L105-L107; Papo, M.J., Catledge, S.A., Vohra, Y.K., Mechanical wear behaviour of nanocrystalline and multilayer diamond coatings on temporomandibular joint implants (2004) J Mater Sci: Mater Med, 15, pp. 773-777; Aspenberg, P., Antilla, A., Konttinen, Y.T., Lappalainen, R., Goodman, S.B., Nordsletten, L., Santavirta, S., Benign response to particles of diamond and SiC: Bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17, pp. 807-812; Nordsletten, L., Hogasen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: In vitro studies of new prosthesis coatings (1996) Biomaterials, 17, pp. 1521-1527; Mitura, S., Mitura, A., Niedzielski, P., Couvrat, P., Nanocrystalline diamond coatings (1999) Chaos Solitons Fractals, 10, pp. 2165-2176; Mitura, K., Niedzielski, P., Grzegorz, B., Moll, J., Walkowiak, B., Pawlowska, Z., Louda, P., Mitura, S., Interactions between carbon coatings and tissue (2006) Surf Coat Technol, 201, pp. 2117-2123; Garguilo, J.M., Davis, B.A., Buddie, M., Köck, F.A.M., Nemanich, R.J., Fibrinogen adsorption onto microwave plasma chemical vapour deposited diamond films (2004) Diamond Relat Mater, 13, pp. 595-599; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour deposited diamond (1995) Biomaterials, 16, pp. 483-488; Narayan, R.J., Wei, W., Jin, C., Andara, M., Agarwal, A., Gerhardt, R.A., Shih, C., Singh, R.N., Microstructural and biological properties of nanocrystalline diamond coatings (2006) Diamond Relat Mater, 15, pp. 1935-1940; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494, pp. 92-97; Nethl, D.S., Kloss, F.R., Haq, M.N.U., Rainer, M., Larsson, K., Linsmeier, C., Köhler, G., Bonn, G., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27, pp. 4547-4556; Silva, V.A., Costa, F.M., Fernandes, A.J.S., Nazaré, M.H., Silva, R.F., Influence of SiC particle addition on the nucleation density and adhesion strength of MPCVD diamond coatings on S13N4 substrates (2000) Diamond Relat Mater, 9, pp. 483-488; Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23, pp. 4897-4906; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond Relat Mater, 12, pp. 733-737; Coelho, M.J., Trigo Cabrai, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing, Part 1: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci: Mater Med, 7, pp. 637-643; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., In vitro evaluation of cell/biomaterial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Ferrari AC, Robertson J. Origin of the 1150 cm -1 Raman mode in nanocrystalline diamond. Phys Rev B 2001;63:121405-1-4Pfeiffer, R., Kuzmany, H., Knoll, P., Bokova, S., Salk, N., Günther, B., Evidence for trans-polyacetylene in nano-crystalline diamond films (2003) Diamond Relat Mater, 12, pp. 268-271; Fernandes, A.J.S., Neto, M.A., Almeida, F.A., Silva, R.F., Costa, F.M., Nano- and micro-crystalline diamond growth by MPCVD in extremely poor hydrogen uniform plasmas (2007) Diamond Relat Mater, 16, pp. 757-761; Almeida, F.A., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Silva, R.F., Nano to micrometric HFCVD diamond adhesion strength to Si 3N 4 (2007) Vacuum, 81, pp. 1443-1447; Abreu, C.S., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Gomes, J.R., Silva, R.F., Enhanced performance of HFCVD nanocrystalline diamond self-mated tribosystems by plasma pretreatments on silicon nitride substrates (2006) Diamond Relat Mater, 15, pp. 2024-2028; Abreu, C.S., Amaral, M., Fernandes, A.J.S., Oliveira, F.J., Silva, R.F., Gomes, J.R., Friction and wear performance of HFCVD nano-crystalline diamond coated silicon nitride ceramics (2006) Diamond Relat Mater, 15, pp. 739-744; Stein, G.S., Lian, J.B., Molecular mechanisms mediated proliferation- differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocr Rev, 14, pp. 424-442; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing, Part 2: Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Form and function of bone (1994) Orthopedic Basic Science, pp. 127-185. , Simon SP, editor, Columbus, OH: American Academy of Orthopedic Surgeons;; Webster, T.J., Ejiofor, J.U., Increased osteoblast adhesion on nanophase metals: Ti, Ti6A14V, and CoCrMo (2004) Biomaterials, 25, pp. 4731-4739; Kay, S., Thapa, A., Haberstroh, K.M., Webster, T.J., Nanostructured polymer/nanophase ceramic composites enhance osteoblast and chondrocyte adhesion (2002) Tissue Eng, 8, pp. 753-761; Webster, T.J., Smith, T.A., Increased osteoblast function on PLGA composites containing nanophase titania (2005) J Biomed Mater Res A, 74, pp. 677-686; Balasundaram, G., Sato, M., Webster, T.J., Using hydroxyapatite nanoparticles and decreased crystallinity to promote osteoblast adhesion similar to functionaizing with RGD (2006) Biomaterials, 27, pp. 2798-2805; Webster, T.J., (2004) Proteins: Structure and interactions patterns to solid surfaces, pp. 1-16. , editors. Encyclopedia of Nanoscience and Nanotechnology. New York: Marcel Dekker; Siegel RW. Creating nanophase materials. Sci Am (Int Ed) 1996;275:74-79Webster, T.J., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Enhanced osteoclast-like cell functions on nano-phase ceramics (2001) Biomaterials, 22, pp. 1327-1333; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nano-phase ceramics (2000) J Biomed Mater Res, pp. 51475-51483; Webster, T.J., Schadler, L.S., Siegel, R.W., Bizios, R., Mechanisms of enhanced osteoblast sdhesion on nanophase alumina involve vitronectin (2001) Tissue Eng, 7, pp. 291-301
Keywords: adult; alkaline phosphatase; ALP activity; Animal cell culture; Architectural acoustics; article; Atomic force microscopy; Biocompatibility; Bone; bone marrow cell; Bone Marrow Cells; Bone Regeneration; Cell culture; cell proliferation; cell survival; Cells; Cells, Cultured; ceramics; Cladding (coating); Coated Materials, Biocompatible; confocal microscopy; controlled study; diamond; Diamonds; enzyme activity; extracellular matrix; human; Human bone marrow cells; human cell; Humans; Imaging techniques; Implants (surgical); In vitro biocompatibility; in vitro selection; Joint replacement; male; Materials characterization; materials testing; Micro-Raman spectroscopy; Microscopic examination; Microscopy, Atomic Force; Microscopy, Confocal; Microscopy, Electron, Scanning; mineralization; MTT assaying; Nano-crystalline diamond; nanocrystal; Nanocrystalline alloys; Nanocrystalline materials; nanoparticles; Nanostructured materials; Nitrides; Nonmetals; osteoblast; Osteoblasts; polystyrene; Prostheses and Implants; Raman spectrometry; Scanning electron microscopy; Secondary emission; Silicon; Silicon compounds; Silicon nitride; Spectrum Analysis, Raman; Surface Properties; Tissue engineering

Omniview-SisPorto® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis - Ayres-de-Campos, D.; Sousa, P.; Costa, A.; Bernardes, J. (Journal of Perinatal MedicineJ. Perinat. Med., 2008)
Visual analysis of cardiotocograms is poorly reproducible and is currently recognized as the main weakness of the STAN® methodology. The Omniview-SisPorto® 3.5 program is the most recent version of a central monitoring system that provides visual and sound alerts, based on computer analysis of cardiotocographic and ST event features. This paper describes the program's main characteristics and provides an overview of the system's online alerts. Omniview-SisPorto® 3.5 is the first central monitoring system to incorporate computerized analysis of cardiotocographic and ST event features, providing health professionals with online alerts for minor and major changes in monitored signals. The system is currently undergoing extensive clinical evaluation. © 2008 by Walter de Gruyter.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2008.030Language of Original Document: EnglishCorrespondence Address: Ayres-De-Campos, D.; Departmento Ginecologia e Obstetricia, Faculdade de Medicina, Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: sisporto@med.up.ptTradenames: Omniview-SisPorto 3.5 system, SpeculumManufacturers: SpeculumReferences: Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) Br J Obstet Gynaecol, 114, pp. 1191-1193;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marquesde-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Bernardes, J., Comparison of fetal heart rate baseline estimation by SisPorto 2.01 and a consensus of clinicians (2004) Eur J Obstet Gynecol Reprod Biol, 117, pp. 174-178; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) Br J Obstet Gynaecol, 114, pp. 1446-1447; Bernardes, J., Moura, C., Marques de, S.J., Pereira Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am J Obstet Gynecol, 177, pp. 1385-1390. , National Institute of Child Health and Human Development Research Planning Workshop; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labor (2006) Cochrane Database of Systematic Reviews, (3); Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; (2001) Evidence-based clinical guideline: The use of electronic fetal monitoring, , RCOG, Royal College of Obstetricians and Gynaecologists, London, RCOG Press; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167
Keywords: article; Cardiotocography; computer program; Computer-assisted; Electrocardiography; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus hypoxia; fetus monitoring; Heart rate; human; Humans; instrumentation; online system; Pregnancy; priority journal; Signal processing; ST segment

Osteoblast adhesion and morphology on TiO 2 depends on the competitive preadsorption of albumin and fibronectin - Sousa, S.R.; Lamghari, M.; Sampaio, P.; Moradas-Ferreira, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
This study aims at assessing the influence of the competitive preadsorption of human serum albumin (HSA) and human plasma fibronectin (FN) from binary solutions and 10% plasma on MC3T3-E1 osteoblast adhesion and morphology on two types of TiO 2 substrates. One was commercially pure titanium with a titanium oxide layer formed in an H 2O 2 solution and the other TiO 2 sputtered on Si (Sousa et al., Langmuir 2004; 20:9745-9754.). The strategy applied in the present investigation was to compare osteoblast adhesion to surfaces preadsorbed with HSA, FN, HSA/FN = 1, HSA/FN = 200, and 10% plasma. The adsorption of proteins was evaluated measuring the amount and the effectiveness of binding with radiolabeled proteins, 125I-FN and 125I-HSA. Our results indicated that MC3T3-E1 osteoblast adhesion correlates well with the amounts of FN and HSA adsorbed on TiO 2 surfaces. Also, we found that fewer osteoblasts adhered to both substrates preadsorbed with HSA, HSA/FN = 200, and 10% plasma, after 4 and 24 h, than to the surfaces preadsorbed with FN and HSA/FN = 1. For the latter, FN was able to compensate the inhibitory effect of HSA on osteoblast adhesion. Therefore, the presence of lower amounts of coadsorbed albumin may improve presentation of FN in a more integrin-recognized conformation, suggesting that some degree of molecular packing prevents loss of integrin-binding activity. FN reversibility does not seem to be dependent on the HSA/FN adsorption mass ratio in solution, suggesting that FN competitively adsorbs to TiO 2 in a favorable conformation and does not suffers subsequent conformational changes allowing exchange with other FN molecules in solution. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31201PubMed ID: 17607748Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomaterials, R. do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ssousa@ibmc.up.ptChemicals/CAS: fibronectin, 86088-83-7; human serum albumin, 9048-49-1; hydrogen peroxide, 7722-84-1; iodine 125, 14158-31-7, 22822-81-7; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; Albumins; Coloring Agents; Fibronectins; Iodine Radioisotopes; Neutral Red, 553-24-2; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681;Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkane-thiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Malmsten, M., Lassen, B., Competitive adsorption at hydrophobic surfaces from binary protein systems (1994) J Colloid Interface Sci, 166, pp. 490-498; Koenig, A.L., Gambillara, V., Grainger, D.W., Correlating fibronectin adsorption with endothelial cell adhesion and signaling on polymer substrates (2003) J Biomed Mater Res A, 64, pp. 20-37; Horbett, T.A., The role of adsorbed proteins in animal cell adhesion (1994) Colloids Surf B, 2, pp. 225-240; Huang, H.H., Ho, C.T., Lee, T.H., Lee, T.L., Liao, K.K., Chen, F.L., Effect of surface roughness of ground titanium on initial cell adhesion (2004) Biomol Eng, 21, pp. 93-97; Vitte, J., Benoliel, A.M., Pierres, A., Bongrand, P., Is there a predictable relationship between surface physical-chemical properties and cell behaviour at the interface? (2004) Eur Cell Mater, 7, pp. 52-63; Tsai, W.B., Grunkemeier, J.M., McFarland, C.D., Horbett, T.A., Platelet adhesion to polystyrene-based surfaces preadsorbed with plasmas selectively depleted in fibrinogen, fibronectin, vitronectin, or von Willebrand's factor (2002) J Biomed Mater Res, 60, pp. 348-359; Grainger, D.W., Pavon-Djavid, G., Migonney, V., Josefowicz, M., Assessment of fibronectin conformation adsorbed to polytetrafluoroethylene surfaces from serum protein mixtures and correlation to support of cell attachment in culture (2003) J Biomater Sci Polym Ed, 14, pp. 973-988; Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-terminated self-assembled monolayers (2005) Biomaterials, 26, pp. 3891-3899; Culp, L.A., Sukenik, C.N., Cell type-specific modulation of fibronectin adhesion functions on chemically-derivatized self-assembled monolayers (1998) J Biomater Sci Polym Ed, 9, pp. 1161-1176; Baugh, L., Vogel, V., Structural changes of fibronectin adsorbed to model surfaces probed by fluorescence resonance energy transfer (2004) J Biomed Mater Res A, 69, pp. 525-534; McClary, K.B., Ugarova, T., Grainger, D.W., Modulating fibroblast adhesion, spreading, and proliferation using self-assembled monolayer films of alkylthiolates on gold (2000) J Biomed Mater Res, 50, pp. 428-439; Sousa, S.R., Moradas-Ferreira, P., Melo, L.V., Saramago, B., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Gehanno, V., Freitas, P.P., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Soares, J.C., Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Iodine-125. A Guide to Radioiodination Techniques. Little Chalfont, UK: Amersham Life Science; 1993. p 64Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; Sousa, S.R., Moradas-Ferreira, P., Barbosa, M., TiO 2 type influences fibronectin adsorption (2005) J Mater Sci Mater Med, 16, pp. 1173-1178; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., Attachment of cultured human bone cells to novel polymers (1999) J Biomed Mater Res, 44, pp. 1-11; McFarland, C.D., Thomas, C.H., DeFilippis, C., Steele, J.G., Healy, K.E., Protein adsorption and cell attachment to patterned surfaces (2000) J Biomed Mater Res, 49, pp. 200-210; Yang, Y.Z., Cavin, R., Ong, J.L., Protein adsorption on titanium surfaces and their effect on osteoblast attachment (2003) J Biomed Mater Res A, 67, pp. 344-349; MacDonald, D.E., Rapuano, B.E., Deo, N., Stranick, M., Somasundaran, P., Boskey, A.L., Thermal and chemical modification of titanium-aluminum-vanadium implant materials: Effects on surface properties, glycoprotein adsorption, and MG63 cell attachment (2004) Biomaterials, 25, pp. 3135-3146; Steele, J.G., Johnson, G., McFarland, C., Dalton, B.A., Gengenbach, T.R., Chatelier, R.C., Underwood, P.A., Griesser, H.J., Roles of serum vitronectin and fibronectin in initial attachment of human vein endothelial-cells and dermal fibroblasts on oxygen-containing and nitrogen-containing surfaces made by radiofrequency plasmas (1994) J Biomater Sci Polym Ed, 6, pp. 511-532; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res A, 66, pp. 247-259; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (1999) J Biomed Mater Res, 49, pp. 435-447; Webb, K., Hlady, V., Tresco, P.A., Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces (2000) J Biomed Mater Res, 49, pp. 362-368; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cell osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation (2005) J Biomed Mater Res A, 75, pp. 387-397; Scotchford, C.A., Gilmore, C.P., Cooper, E., Leggett, G.J., Downes, S., Protein adsorption and human osteoblast-like cell attachment and growth on alkylthiol on gold self-assembled monolayers (2002) J Biomed Mater Res, 59, pp. 84-99; Pettit, D.K., Horbett, T.A., Hoffman, A.S., Influence of the substrate binding characteristics of fibronectin on corneal epithelial cell outgrowth (1992) J Biomed Mater Res, 26, pp. 1259-1275; Steele, J.G., Johnson, G., Underwood, P.A., Role of serum vitronectin and fibronectin in adhesion of fibroblasts following seeding onto tissue-culture polystyrene (1992) J Biomed Mater Res, 26, pp. 861-884
Keywords: 2; 3T3 Cells; Adsorption; Albumins; animal cell; Animals; article; binding kinetics; cell adhesion; Coloring Agents; Competitive protein adsorption; controlled study; cytoskeleton; Data Interpretation, Statistical; Fibronectin; Fibronectins; FN; HSA; human serum albumin; hydrogen peroxide; iodine 125; Iodine Radioisotopes; isotope labeling; Mice; Microscopy, Confocal; mouse; neutral red; nonhuman; osteoblast; Osteoblast adhesion; Osteoblasts; Protein radiolabeling; Proteins; Radiology; Solutions; Sterilization; surface property; TiO; Titanium; Titanium dioxide

PLD bioactive ceramic films: The influence of CaO-P 2O 5 glass additions to hydroxyapatite on the proliferation and morphology of osteblastic like-cells - Oliveira, G.M.; Ferraz, M.P.; González, P.G.; Serra, J.; Leon, B.; Pèrez-Amor, M.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2008)
This work consists on the evaluation of the in vitro performance of Ti6Al4V samples PLD (pulsed laser deposition) coated with hydroxyapatite, both pure and mixed with a CaO-P 2O 5 glass. Previous studies on immersion of PLD coatings in SBF, showed that the immersion apatite films did not present the usual cauliflower morphology but replicated the original columnar structure and exhibited good bioactivity. However, the influence of glass associated to hydroxyapatite concerning adhesion, proliferation and morphology of MG63 cells on the films surface was unclear. In this study, the performance of these PLD coated samples was evaluated, not only following the physical-chemical transformations resulting from the SBF immersion, but also evaluating the cytocompatibility in contact with osteoblast-like MG63 cells. SEM and AFM confirmed that the bioactive ceramic PLD films reproduce the substrate's surface topography and that the films presented good adherence and uniform surface roughness. Physical-chemical phenomena occurring during immersion in SBF did not modify the original columnar structure. In contact with MG63 cells, coated samples exhibited very good acceptance and cytocompatibility when compared to control. The glass mixed with hydroxyapatite induced higher cellular proliferation. Cells grown on these samples presented many filipodia and granular structures, typical features of osteoblasts. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3331-zPubMed ID: 18058197Language of Original Document: EnglishCorrespondence Address: Oliveira, G. M.; Universidade Fernando Pessoa, Praça Nove de Abril 349, 4249-004 Porto, Portugal; email: gisela@ufp.ptChemicals/CAS: calcium oxide, 1305-78-8; hydroxyapatite, 1306-06-5, 51198-94-8; oxide, 16833-27-5; Biocompatible Materials; Calcium Compounds; Ceramics; Durapatite, 1306-06-5; Oxides; Phosphorus Compounds; Polystyrenes; lime, 1305-78-8; phosphorus pentoxide, 1314-56-3References: Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487;Hench, L.L., (1998) Biomaterials, 19, p. 1419; Park, S.H., Llinás, A., Goel, V.K., Keller, J.C., (2000) The Biomedical Engineering Handbook, , Edited by: J. D. BRONZINO (CRC Press, LLC, Boca Raton); Hench, L.L., (1994) 7th International Symposium on Ceramics in Medicine, p. 3. , Edited by: Ö. H. A. A. Y. URPO (Butterworth-Heinemann Ltd Oxford, England); Kokubo, T., (1991) Biomaterials, 12, p. 155; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, p. 6. , JAAS Takayan Press. Ishiyaku euroAmerica, Inc Tokyo; Orlovskii, V.P., Komlev, V.S., Barinov, S.M., (2002) Inorg. Mater., 38, p. 973; Kenny, S.M., Buggy, M., (2003) J. Mater. Sci. Mat. Med., 14, p. 923; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mat. Sci. Mat. Med., 6, p. 348; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci.: Mater. Med., 12, p. 629; Ferraz, M.P., Monteiro, F.J., Gião, D., Léon, B., Gonzalez, P., Liste, S., Serra, J., Perez-Amor, M., (2004) Key Eng. Mat., 254-256, p. 347; Porter, A.E., Hobbs, L.W., Benezra Rosen, V., Spector, M., (2002) Biomaterials, 23, p. 725; Kim, H.-K., Jang, J.-W., Lee, C.-H., (2004) J. Mater. Sci.: Mater. Med., 15, p. 825; Harada, Y., Wang, J.-T., Doppalapudi, V.A., Willis, A.A., Jasty, M., Harris, W.H., Nagase, M., Goldring, S.R., (1996) J. Biomed. Mater. Res., 31, p. 19; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2000) Appl. Surf. Sci., 154-155, p. 434; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1996) J. Mater. Sci.: Mater. Med., 7, p. 187; Arias, J.L., Mayor, M.B., Pou, J., Leng, Y., Léon, B., Pérez-Amor, M., (2003) Biomaterials, 24, p. 3403; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2002) Appl. Surf. Sci., 182, p. 448; Arias, J.L., Mayor, M.B., Pou, J., Léon, B., Pérez-Amor, M., (2002) Vaccum, 67, p. 653; Arias, J.L., Garcia-Sanz, F.J., Mayor, M.B., Chiussi, S., Pou, J., Léon, B., Pérez-Amor, M., (1998) Biomaterials, 19, p. 883; Mayor, M.B., Arias, J.L., Chiussi, S., Garcia, F., Pou, J., Léon, B., Pérez-Amor, M., (1998) Thin Solid Films, 317, p. 363; Kokubo, T., Kushitani, H., Sakka, S., Kitsuki, T., Yamamuro, T., (1990) J. Biomed. Mater. Res., 24, p. 721; Monteiro, F.J., Ferraz, M.P., Gião, D., Leon, B., Gonzalez, P., Liste, S., Serra, J., Perez-Amor, M., (2002) 17th European Conference on Biomaterials, pp. P65. , Edited by: E. S. F. Biomaterials (Barcelona, Spain); Lossdörfer, S., Schwartz, Z., Wang, L., Lohmann, C.H., Turner, J.D., Wieland, M., Cochran, D.L., Boyan, B.D., (2004) J. Biomed. Mater. Res, 70, p. 361; Bannister, S.R., Lohmann, C.H., Liu, Y., Sylvia, V.L., Cochran, D.L., Dean, D.D., Boyan, B.D., Schwartz, Z., (2002) J. Biomed. Mater. Res., 60, p. 164; Cleries, L., Fernandez-Pradas, J.M., Sardin, G., Morenza, J.L., (1998) Biomaterials, 19, p. 1483; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci.: Mater. Med., 7, p. 21; Knabe, C., Klar, F., Fitzner, R., Radlanski, R.J., Gross, U., (2002) Biomaterials, 23, p. 3235; Garcia, F., Arias, J.L., Mayor, M.B., Pou, J., Rehman, I., Knowles, J., Best, S., Bonefield, W., (1998) J. Biomed. Mater. Res. (Appl. Biomater), 43, p. 69; Peng, P., Kumar, S., Voelcker, N.H., Szili, E., Smart, R.S.C., Griesser, H.J., (2006) J. Biomed. Mater. Res., 76, p. 347; Borsari, V., Giavaresi, G., Fini, M., Torriceli, P., Salito, A., Chiesa, R., Chiusoli, L., Giardino, R., (2005) J. Biomed. Mater. Res. Part B: Appl. Biomater., 75, p. 359; Massaro, C., Baker, M.A., Cosentino, F., Ramires, P.A., Klose, S., Milella, E., (2001) J. Biomed. Mater. Res., 58, p. 651; Bigi, A., Bracci, B., Cuisinier, F., Elkaim, R., Fini, M., Mayer, I., Mihailescu, I.N., Torricelli, P., (2005) Biomaterials, 26, p. 2381; Zeng, H., Lacefield, W.R., (2000) J. Biomed. Mater. Res., 50, p. 239; Clèries, L., Fernandez-Pradas, J.M., Morenza, J.L., (2000) Biomaterials, 21, p. 1861; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 45, p. 376; Li, P., Ducheyne, P., (1998) J. Biomed. Mater. Res., 41, p. 341; Weng, J., Liu, Q., Wolke, J.G., Zhang, X., De Groot, K., (1997) Biomaterials, 18, p. 1027; Tas, A.C., (2000) Biomaterials, 21, p. 1429; Kokubo, T., Kim, H.-M., Kawashita, M., (2003) Biomaterials, 24, p. 2161; Dewez, J.-L., Doren, A., Schneider, Y.-J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Anselme, K., Linez, P., Bigerelle, M., Le Maguer, D., Le Maguer, A., Hardouin, P., Hildebrand, H.F., Leroy, J.M., (2000) Biomaterials, 21, p. 1567; Okumura, A., Goto, M., Goto, T., Yoshinari, M., Masuko, S., Katsuki, T., Tanaka, T., (2001) Biomaterials, 22, p. 2263; Kim, H.J., Kim, S.H., Kim, M.S., Lee, E.J., Oh, H.G., Oh, W.M., Park, S.W., Dean, D.D., (2005) J. Biomed. Mater. Res., 74, p. 366
Keywords: Apatite; Apatite films; Bioactive ceramic films; Bioactive glass; Bioactivity; Bioceramics; Biocompatible Materials; Biofilms; Brassica oleracea var. botrytis; Calcium Compounds; calcium oxide; Cauliflower morphology; cell adhesion; cell proliferation; cell structure; cell survival; ceramics; Columnar structure; conference paper; controlled study; Durapatite; glass; human; human cell; Humans; hydroxyapatite; Lasers; materials testing; Microscopy, Atomic Force; Microscopy, Electron, Scanning; morphology; osteoblast; Osteoblasts; oxide; Oxides; phosphorous pentoxide; Phosphorus Compounds; Polystyrenes; priority journal; Pulsed laser deposition; unclassified drug

Region and graph-based motion segmentation - Monteiro, F.C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2008)
This paper describes an approach for integrating motion estimation and region clustering techniques with the purpose of obtaining precise multiple motion segmentation. Motivated by the good results obtained in static segmentation we propose a hybrid approach where motion segmentation is achieved within a region-based clustering approach taken the initial result of a spatial pre-segmentation and extended to include motion information. Motion vectors are first estimated with a multiscale variational method applied directly over the input images and then refined by incorporating segmentation results into a region-based warping scheme. The complete algorithm facilitates obtaining spatially continuous segmentation maps which are closely related to actual object boundaries. A comparative study is made with some of the best known motion segmentation algorithms. © 2008 Springer-Verlag Berlin Heidelberg.
Conference code: 72695Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-540-69812-8_60Language of Original Document: EnglishCorrespondence Address: Monteiro, F. C.; INEB - Instituto de Engenharia BiomédicaPortugalReferences: Ayer, S., Sawhney, U.S.: Layered representation of motion video using robust maximum-likelihood estimation of mixture models and mdl encoding. In: Proc. IEEE International Conference on Computer Vision, June 1995, pp. 777-784 (1995)Brox, T., (2005) From pixels to regions: Partial differential equation in image analysis, , PhD thesis, Department of Mathematics and Computer Science, Saarland University, Germany;Brox, T., Bruhn, A., Papenberg, N., Weickert, J.: High Accuracy Optical Flow Estimation Based on a, Theory for Warping. In: Pajdla, T., Matas, J(G.) (eds.) ECCV 2004. LNCS, 3024, pp. 25-36. Springer, Heidelberg (2004)Bruhn, A., Weickert, J., Schnörr, C., Lucas/Kanade meets Horn/ Schunck: Combining local and global optic flow methods (2005) International Journal of Computer Vision, 61 (3), pp. 1-21; Chang, S.-F., Sikora, T., Puri, A., Overview of the MPEG-7 standard (2001) IEEE Transactions on Circuits and Systems for Video Technology, 11 (6), pp. 688-695; Horn, B.K.P., Schunck, B.G., Determining optical flow (1981) Artificial Intelligence, 17 (1-3), pp. 185-203; Monteiro, F.C., (2007) Region-based spatial and temporal image segmentation, , PhD thesis, Faculdade de Engenharia da Universidade do Porto, Portugal; Monteiro, F.C., Campilho, A.: Spectral Methods in Image Segmentation: A Combined Approach. In: Marques, J.S., Pérez de la Blanca, N., Pina, P. (eds.) IbPRIA 2005. LNCS, 3523, pp. 191-198. Springer, Heidelberg (2005)MPEG4. MPEG-4 video verification model, version 15.0. ISO/IEC/JTC1/SC29/WG11 N3093 1999Papenberg, N., Bruhn, A., Brox, T., Didas, S., Weickert, J., Highly accurate optic flow computation with theoretically justified warping (2006) Int. Journal of Computer Vision, 67 (2), pp. 141-158; Shi, J., Malik, J., Motion segmentation and tracking using normalized cuts (1998) Proc. of IEEE Int. Conference on Computer Vision, pp. 1154-1160; Smith, P., (2001) Edge-based motion segmentation, , PhD thesis, Department of Engineering, University of Cambridge; Vasconcelos, N., Lippman, A., Empirical bayesian motion segmentation (2001) IEEE Transactions on Pattern Analysis and Machine Intelligence, 23 (2), pp. 217-221; Wang, J., Adelson, E., Representing moving images with layers (1994) IEEE Transactions on Image Processing, 3 (5), pp. 625-638; Weiss, Y., Adelson, E.H., A unified mixture framework for motion segmentation: Incorporating spatial coherence and estimating the number of models (1996) Proc. of IEEE International Conference on Computer Vision and Pattern Recognition, pp. 321-326. , San Francisco, USA, June
Keywords: Clustering approach; Comparative studies; Conformal mapping; Estimation; Flow of solids; Graph-based; Heidelberg (CO); Hybrid approaches; Image analysis; Image segmentation; Imaging techniques; Input Images; International conferences; Maps; Motion estimation; Motion information; Motion segmentation; Motion vector (MV); Multi scaling; Multiple motion segmentation; Object boundaries; Region clustering; Region-based; Segmentation maps; Segmentation results; Static segmentation; Variational methods

Structural studies of Na 2O-TiO 2-CaO-P 2O 5 system glasses investigated by FTIR and FT-Raman - Li, Y.; Weng, W.; Santos, J.D.; Lopes, A.M. (Physics and Chemistry of Glasses: European Journal of Glass Science and Technology Part BPhys. Chem. Glasses Euro. J. Glass Sci. Technol. Part B, 2008)
CaO-P 2O 5 based glasses are widely used as biomaterials due to their various chemical compositions, excellent bioactivity, adjustable biodegradation and suitable mechanical properties. The structures of Na 2O-TiO 2-CaO-P 2O 5 system glasses were investigated by FTIR and FT-Raman spectroscopies. The calcium phosphate glasses have chain-like structures based on Ti-O-P linkages containing [P 2O 7] 4- groups and [PO 4] 3- groups. Some amount of TiO 2 enters into the glass network, in which [TiO 4] tetrahedra connect with [PO 4] tetrahedra through the P-O-Ti bonds, the remaining TiO 2 exists into interspaces of [PO 4] tetrahedra. CaO connects the two linkages in the form of Ca-O-P bonds.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Li, Y.; College of Materials Science and Engineering, Nanjing University of Technology, Nanjing, 210009, China; email: lyanbao@163.comReferences: Hench, L.L., Glasses to turn on genes (2004) Glass Sci. Technol, 77, pp. 95-103;Hench, L.L., Third-generation gene-activating biomaterials (2003) Thermec'2003, Pts 1-5, pp. 179-184; Knowles, J.C., Phosphate based glasses for biomedical applications (2003) J. Mater. Chem, 13 (10), pp. 2395-2401; Hench, L.L., Xynos, I.D., Polak, J.M., Bioactive glasses for in situ tissue regeneration (2004) J. Biomater. Sci.-Polym. Ed, 15 (4), pp. 543-562; Kasuga, T., Bioactive calcium pyrophosphate glasses and glass-ceramics (2005) Acta Biomater, 1 (1), pp. 55-64; Rawson, H., Inorganic Glass-Forming System, Academic Press, London, YEAR, p. 155; Selvaraj, U., Rao, K.J., (1988) J. Non-Cryst. Solids, 104, p. 300; Chakraborty, S., Paul, A., (1989) J. Mater. Sci. Lett, 8, p. 1358; Shih, P.Y., Yung, S.W., Chin, T.S., (1999) J. Non-Cryst. Solids, 244, p. 211; Brow, R.K., (1997) Phys. Chem. Glasses, 38, p. 300; Kasuga, T., Abe, Y., Calcium phosphate invert glasses with soda and titania (1999) J. Non-Cryst. Solids, 243 (1), pp. 70-74; Kasuga, T., Abe, Y., Novel calcium phosphate ceramics prepared by powder sintering and crystallization of glasses in the pyrophosphate region (1998) J. Mater. Res, 13 (12), pp. 3357-3360; Zhang, Y., Santos, J.D., Microstructural characterisation and in vitro apatite formationof CaO-P 2O 5-TiO 2-MgO-Na 2O glass-ceramics (2001) J. Eur. Ceram. Soc, 21 (2), pp. 169-175; Rehman, I., Bonfield, W., Characterization of hydroxyapatite and carbonated apatite by photo acoustic FTIR spectroscopy (1997) J. Mater. Sci.-Mater. Med, 8 (1), pp. 1-4; Farrow, L.A., Vogel, E.M., (1992) J. Non-Crystal. Solids, 143, p. 59; Li, Y., (2003) J. Chin. Ceram. Soc, 31, p. 669. , in Chinese; Hudgens, J.J., Martin, S.W., (1993) J. Am. Ceram. Soc, 76, p. 1691; Brow, R.K., Tallant, D.R., Myers, S.T., Phifer, C.C., (1995) J. Non-Crystal. Solids, 191, p. 45; Bobovish, Y.S., (1962) Opt. Spect. (English Transl.), 13, p. 274; Nelson Jr, L.S., Amorphous calcium phosphates of different composition give very similar EXAFS spectra (1989) Phys. B: Cond. Matter, 158 (1-3), pp. 105-106; Stranford, T.C., Condrate, R.A., Cornilsen, B.C., (1981) J. Molec. Struct, 73, p. 231; Wazer, J.R.V., (1958) Phosphorus and its Compounds, 1. , Interscience, New York; Brow, R.K., (1994) J. Non-Crysl. Solids, 177, p. 221; Tatsumisago, M., Kowada, Y., Minami, T., (1988) Phys. Chem. Glasses, 29, p. 63; Meyer, K., (1998) Phys. Chem. Glasses, 39, p. 108; Ed., J. A. D. Lange's Handbook of Chemistry, Third edition, McGraw-Hill Book Company, 1985. p. 3-117, p3-123Iwamoto, N., (1986) Yogyo-Kyokai-Shi, 94, p. 856. , in Japanese

Surface characterization and cell response of a PLA/CaP glass biodegradable composite material - Navarro, M.; Engel, E.; Planell, J.A.; Amaral, I.; Barbosa, M.; Ginebra, M.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
Bioabsorbable materials are of great interest for bone regeneration applications, since they are able to degrade gradually as new tissue is formed. In this work, a fully biodegradable composite material containing polylactic acid (PLA) and calcium phosphate (CaP) soluble glass particles has been characterized in terms of surface properties and cell response. Cell cultures were performed in direct contact with the materials and also with their extracts, and were evaluated using the MTT assay, alkaline phosphatase activity, and osteocalcin measurements. The CaP glass and PLA were used as reference materials. No significant differences were observed in cell proliferation with the extracts containing the degradation by-products of the three materials studied. A relation between the materials wettability and the material-cell interactions at the initial stages of contact was observed. The most hydrophilic material (CaP glass) presented the highest cell adhesion values as well as an earlier differentiation, followed by the PLA/glass material. The incorporation of glass particles into the PLA matrix increased surface roughness. SEM images showed that the heterogeneity of the composite material induced morphological changes in the cells cytoskeleton. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31546PubMed ID: 17729262Language of Original Document: EnglishCorrespondence Address: Ginebra, M. P.; Department of Materials Science, Institute of Bioengineering of Catalonia (IBEC), Technical University of Catalonia, Avda Diagonal 647, 08028-Barcelona, Spain; email: maria.pau.ginebra@upc.eduChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; osteocalcin, 136461-80-8; polylactic acid, 26100-51-6; Alkaline Phosphatase, EC 3.1.3.1; Bone Substitutes; calcium phosphate, 10103-46-5; Calcium Phosphates; Lactic Acid, 50-21-5; Osteocalcin, 104982-03-8; poly(lactic acid), 26100-51-6; PolymersReferences: Barrows, T., Degradable implants materials: A review of synthetic absorbable polymers and their applications (1986) Clin Mater, 1, pp. 233-267;Ciccone, W., Motz, C., Bentley, C., Tasto, J., Bioabsorbable implants in orthopaedics: New developments and clinical applications (2001) J Am Acad Orthop Surg, 9, pp. 280-288; Dunn, R.L., Clinical applications and update on the poly (alpha-hydroxy acids) (1995) Biomedical Applications of Synthetic Biodegradable Polymers, pp. 17-31. , Hollinger JO, editor, Boca Raton: CRC Press;; Middleton, J.C., Tipton, A.J., Synthetic biodegradable polymers as orthopedic devices (2000) Biomaterials, 21, pp. 2335-2346; Böstman O Current concepts review. Absorbable implants for fracture fixation. J Bone Joint Surgery 1991;73A:148-153Ashammakhi, N., Suuronen, R., Tiainen, J., Tormala, P., Waris, T., Spotlight on naturally absorbable osteofixation devices (2003) J Craniofac Surg, 14, pp. 247-259; Hou, Q.P., Grijpma, D.W., Feijen, J., Porous polymeric structures for tissue engineering prepared by a coagulation, compression moulding and salt leaching technique (2003) Biomaterials, 24, pp. 1937-1947; Kellomaki, M., Niiranen, H., Puumanen, K., Ashammakhi, N., Waris, T., Tormala, P., Bioabsorbable scaffolds for guided bone regeneration and generation (2000) Biomaterials, 21, pp. 2495-2505; Mooney, D.J., Park, S., Kaufmann, P.M., Sano, K., Mcnamara, K., Vacanti, J.P., Langer, R., Biodegradable sponges for hepatocyte transplantation (1995) J Biomed Mater Res, 29, pp. 959-965; Ragel, C.V., Vallet-Regi, M., In vitro bioactivity and gentamicin release from glass-polymer-antibiotic composites (2000) J Biomed Mater Res, 51, pp. 424-429; Kohn, J., Langer, R., Bioabsorbable and bioerodible materials (1996) Biomaterials Science, pp. 64-72. , Ratner BD, Hoffman A, Schoen F, Lemons J, editors, New York: Academic Press;; Navarro, M., Ginebra, M.P., Clement, J., Martinez, S., Avila, G., Planell, J.A., Physicochemical degradation of titania-stabilized soluble phosphate glasses for medical applications (2003) J Am Ceram Soc, 86, pp. 1345-1352; Navarro, M., Ginebra, M.P., Planell, J.A., Barrias, C.C., Barbosa, M., In vitro degradation behavior of a novel bioabsorbable composite material based on PLA and a soluble CaP glass (2005) Acta Biomaterialia, 1, pp. 411-419; Stephansson, S.N., Byers, B.A., Garcia, A.J., Enhanced expression of the osteoblastic phenotype on substrates that modulate fibronectin conformation and integrin receptor binding (2002) Biomaterials, 23, pp. 2527-2534; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res A, 66, pp. 247-259; Beumer, G., van Blitterswijk, C., Bakker, D., Ponec, M., Cell-seeding and in vitro biocompatibility evaluation of polymeric matrices of PEO/PBT copolymers and PLLA (1993) Biomaterials, 14, pp. 598-604; Ishaug, S., Yaszemski, M., Bizios, R., Mikos, A., Osteoblast function on synthetic biodegradable polymers (1994) J Biomed Mater Res, 28, pp. 1445-1453; Navarro, M., Ginebra, M.P., Planell, J.A., Cellular response to calcium phosphate glasses with controlled solubility (2003) J Biomed Mater Res A, 67, pp. 1009-1015; Huffman, K.R., Casey, D.J., Effect of carboxyl end groups on hydrolysis of polyglycolic acid (1985) J Polym Sci A: Polym Chem, 23, pp. 1939-1954; Ishaug-Riley, S.L., Okun, L.E., Prado, G., Applegate, M.A., Ratcliffe, A., Human articular chondrocyte adhesion and proliferation on synthetic biodegradable polymer films (1999) Biomaterials, 20, pp. 2245-2256; Park, A., Griffith, L., In vitro cell response to differences in poly-1-lactide crystallinity (1996) Biomaterials, 31, pp. 117-130; Cai, K.Y., Yao, K.D., Lin, S.B., Yang, Z.M., Li, X.Q., Xie, H.Q., Poly (D, L-lactic acid) surfaces modified by silk fibroin: Effects on the culture of osteoblast in vitro (2002) Biomaterials, 23, pp. 1153-1160; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Vogler, E.A., Structure and reactivity of water at biomaterial surfaces (1998) Adv Colloid Interface Sci, 74, pp. 69-117; Vogler, E.A., Interfacial chemistry in biomaterials science (1993) Surfactant Science Series, pp. 183-250. , Berg JC, editor. Wettability, Marcel Dekker, New York; Charles-Harris, M., Navarro, M., Engel, E., Aparicio, C., Ginebra, M.P., Planell, J., A Surface characterisation of completely degradable composite scaffolds (2005) J Mater Svi: Mater Med, 16, pp. 1125-1130; Lampin, M., WarocquierClerout, R., Legris, C., Degrange, M., SigotLuizard, M.F., Correlation between substratum roughness and wettability, cell adhesion, and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Khang, G., Jeon, J.H., Lee, L.W., Cho, S.C., Lee, H.B., Cell and platlet adhesion on plasma glow discharge-treated poly(lactide-co-glycolide) (1997) Biomed Mater Engl, 7, pp. 357-368; Webb, K., Hlady, V., Tresco, P.A., Relative importance of surface wettability and charged functional groups on NIH 3T3 fibroblast attachment, spreading, and cytoskeletal organization (1998) J Biomed Mater Res, 41, pp. 422-430; Owen, T.A., Aronow, M., Shalhoub, V., Barone, L.M., Wilming, L., Tassinari, M.S., Progressive development of the rat osteoblast phenotype in vitro - Reciprocal relationships in expression of genes associated with osteoblast proliferation and differentiation during formation of the bone extracellular-matrix (1990) J Cell Physiol, 143, pp. 420-430; Lian, J.B., Stein, G.S., Concepts of osteoblast growth and differentiation - Basis for modulation of bone cell-development and tissue formation (1992) Crit Rev Oral Biol Med, 3, pp. 269-305; Quarles, L.D., Yohay, D.A., Lever, L.W., Caton, R., Wenstrup, R.J., Distinct proliferative and differentiated stages of murine Mc3T3-E1 cells in culture - An in vitro model of osteoblast development (1992) J Bone Miner Res, 7, pp. 683-692; Boyan, B.D., Dean, D.D., Lohmann, C.H., Cochran, D.L., Sylvia, V.L., Schwartz, Z., The titanium-bone cell interface in vitro: The role of the surface in promoting osteointegration (2001) Titanium in Medicine, pp. 562-585. , Brunette D, Tengvall P, Textor M, Thomsen P, editors, Berlin: Springer-Verlag;; Gronowicz, G., McCarthy, M.B., Ahmad, M., Direct integrin-mediated attachment of human osteoblasts to implants (1996) J Bone Miner Res, 11, pp. S323; Boyan, B.D., Hummert, T.W., Kieswetter, K., Schraub, D., Dean, D.D., Schwartz, Z., Effect of titanium surface characteristics on chondrocytes and osteoblasts in vitro (1995) Scan Electron Microsc, 5, pp. 323-335; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Effect of titanium surface-roughness on proliferation. Differentiation, and protein-synthesis of human osteoblast-like cells (MG63) (1995) J Biomed Mater Res, 29, pp. 389-401
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorbable Implants; alkaline phosphatase; article; Biodegradable composite materials; biodegradable implant; Biodegradation; Bone; Bone Regeneration; Bone Substitutes; calcium phosphate; Calcium phosphates; cell adhesion; Cell culture; cell function; cell interaction; Cell Line; cell proliferation; Cell response; Composite materials; cytoskeleton; glass; human; human cell; Humans; hydrophilicity; hydrophobicity; In vitro test; Lactic Acid; materials testing; Osteoblasts; osteocalcin; polylactic acid; Polymers; scanning electron microscope; Surface analysis; Surface Properties; wettability

Synthesis and cytocompatibility of porous chitosan-silicate hybrids for tissue engineering scaffold application - Shirosaki, Y.; Okayama, T.; Tsuru, K.; Hayakawa, S.; Osaka, A. (Chemical Engineering JournalChem. Eng. J., 2008)
Chitosan-silicate hybrids with 3D porous structures were prepared with freeze-drying precursor solutions derived from chitosan and γ-glycidoxypropyltrimethoxysilane (GPTMS). They were formed easily in any shape, such as sheets, pellets, disks, granules, and even roll-cakes. The pore size was strongly dependent on the freezing temperature: lower freezing temperature resulted smaller pores, about 110 μm for the hybrids frozen at -20 °C, and about 50 μm for those at -85 °C. The pore size was little dependent on the GPTMS content. In contrast, the GPTMS content affected porosity a littlie: ∼80% for chitosan, and ∼90% for the GPTMS-containing hybrids. Thus, their porous microstructure was controllable due to the freezing temperature and composition. MG63 osteoblastic cells were cultured up to 7 days on the porous hybrids. The cells adhered on the pore walls, proliferated, and migrated deep into the pore structure. It was thus concluded that the present chitosan-silicate hybrids were promising for tissue engineering scaffold applications. © 2007 Elsevier B.V. All rights reserved.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: CMEJAdoi: 10.1016/j.cej.2007.10.012Language of Original Document: EnglishCorrespondence Address: Osaka, A.; Graduate School of Natural Science and Technology, Okayama University, Okayama, 700-8530, Japan; email: osaka@cc.okayama-u.ac.jpReferences: Tateishi, T., Chen, G., Ushida, T., Biodegradable porous scaffolds for tissue engineering (2002) J. Artif. Organs, 5, pp. 77-83;Lee, Y.-K., Mooney, J.D., Hydrogels for tissue engineering (2001) Chem. Rev., 101, pp. 1869-1879; Park, S.-N., Park, J.-C., Kim, H.-O., Song, M.-J., Suh, H., Characterization of porous collagne/hyaluronic acid scaffold modified by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide cross-linking (2002) Biomaterials, 23, pp. 1205-1212; Kuo, C.-K., Ma, P.-X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering: Part 1. Structure, gelation rate and mechanical properties (2001) Biomaterials, 22, pp. 511-521; Widmer, M.S., Gupta, P.K., Lu, L., Meszlenyi, R.K., Evans, G.R.D., Brandt, K., Savel, T., Mikos, A.G., Manufacture of porous biodegradable polymer conduits by an extrusion process for guided tissue regeneration (1998) Biomaterials, 19, pp. 1945-1955; Wang, Y.-C., Lin, M.-C., Wang, D.-M., Hsieh, H.-J., Fabrication of a novel porous PGA-chitosan hybrid matrix for tissue engineering (2003) Biomaterials, 24, pp. 1047-1057; Park, Y.-J., Lee, M.-Y., Lee, J.-Y., Seol, Y.-J., Chung, C.-P., Lee, S.-J., Controlled release of platelet-derived growth factor-BB from chondroitin sulfate-chitosan sponge for guided bone regeneration (2000) J. Control. Release, 67, pp. 385-394; Lee, J.-Y., Nam, S.-H., Im, S.-Y., Park, Y.-J., Lee, Y.-M., Seol, Y.-J., Chung, C.-P., Lee, S.-J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J. Control. Release, 78, pp. 187-197; Wan, Y., Wu, H., Wen, D., Porous-conductive chitosan scaffolds for tissue engineering: 1. Preparation and characterization (2004) Macromol. Biosci., 4, pp. 882-890; Li, J., Pan, J., Zhang, L., Guo, X., Yu, Y., Culture of primary rat hepatocytes within porous chitosan scaffolds (2003) J. Biomed. Mater. Res., 67 A, pp. 938-943; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J. Non-Cryst. Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrids membranes (2005) Biomaterials, 26, pp. 485-493; Hua, H., Jie, W., Changshengh, L., Development of asymmetric gradational-changed porous chitosan membrane for guided periodontal tissue regeneration (2007) Compos. B, 38, pp. 311-316; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-5911; Kang, H.-W., Tabata, Y., Ikada, Y., Fabrication of porous gelatin scaffolds for tissue engineering (1999) Biomaterials, 20, pp. 1339-1344; Ho, M.-H., Kuo, P.-Y., Hsieh, H.-J., Hsien, T.-Y., Hou, L.-T., Lai, J.-Y., Wang, D.-M., Preparation of porous scaffolds by using freeze-extraction and freeze-gelation methods (2004) Biomaterials, 25, pp. 129-138
Keywords: chitosan; Cytocompatibility; GPTMS; Organic-inorganic hybrid; Osteoblastic cell MG63; Osteoblasts; Pore size; Pore structure; Scaffold; Silicates; Tissue engineering; γ-Glycidoxypropyltrimethoxysilane (GPTMS)

Three dimensional macroporous calcium phosphate scaffolds for bone tissue engineering - Teixeira, S.; Oliveira, S.; Ferraz, M.P.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2008)
Calcium phosphate ceramics are widely used as bone substitutes since they are biocompatible and bioactive. Having a chemical composition close to natural bone, calcium phosphate ceramics are promising bone substitute materials in orthopaedics, maxillofacial surgery and dentistry. Hydroxyapatite (HA) and tricalcium phosphate (TCP) are the most commonly used calcium phosphates, because their calcium/phosphorus (Ca/P) ratios are close to that of natural bone and they are relatively stable in physiological environment. HA is a major constituent of bone materials and is resorbed after a long time of residence in the body. In this work, highly porous hydroxyapatite scaffolds were produced by polymer replication method and their properties evaluated by Scanning Electron Microscopy (SEM) and micro computerized tomography (μ-CT).
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Teixeira, S.; INEB, Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: smsilva@ineb.up.ptReferences: Rose, F.R., Cyster, L.A., Grant, D.M., Scotchford, C.A., Howdle, S.M., Shakesheff, K.M.K.M., In vitro assessment of cell penetration into porous hydroxyapatite scaffolds with a central aligned channel (2004) Biomaterials, 25 (24), pp. 5507-5514;Anthony, C., Analysis of 3D bone ingrowth into polymer scaffolds via micro-computed tomography imaging (2004) Biomaterials, 25 (20), pp. 4947-4954; Teixeira, S., Fernandes, H.M., de Boer, J., Ferraz, M.P., Monteiro, F.J., Mesenchymal stem cell proliferation and morphological analysis on interconnected macroporous structures (2007) Key Engineering Materials, 330-332, pp. 1129-1132. , Vols
Keywords: Biocompatibility; Bone; calcium phosphate; Calcium phosphates; Computerized tomography; Maxillofacial prostheses; Maxillofacial surgery; Micro computerized tomography; Porous; Scaffolds; Scanning electron microscopy; Tissue engineering

Tracking of Arabidopsis thaliana root cells in time-lapse microscopy - Marcuzzo, M.; Quelhas, P.; Mendonça, A.M.; Campilho, A. (Proceedings - International Conference on Pattern RecognitionProc. Int. Conf. Pattern Recognit., 2008)
In vivo observation of cells in the Arabidopsis thaliana root, by time-lapse confocal microscopy, is central to biology research. The research herein described is based on large amount of image data, which must be analyzed to determine the location and state of individual cells. Automating the process of cell tracking is an important step to create tools which will facilitate the analysis of cells' evolution through time. Here we introduce a confocal tracking system designed in two stages. At the image acquisition stage, we track the area under analysis based on point-to-point correspondences and motion estimation. After image acquisition, we compute cell-to-cell correspondences through time. The final result is a temporal structured information about each cell. © 2008 IEEE.
Conference code: 81859Export Date: 21 November 2012Source: ScopusArt. No.: 4761746CODEN: PICRELanguage of Original Document: EnglishCorrespondence Address: Marcuzzo, M.; INEB - Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUPPortugalReferences: Beemster, G., Baskin, T., Analysis of cell division and elongation underlying the developmental acceleration of root growth in arabidopsis thaliana (1998) Plant Physiology, 116, pp. 1515-1526;Campilho, A., Garcia, B., Toorn, H., Wijk, H., Campilho, A., Scheres, B., Time-lapse analysis of stem-cell divisions in the arabidopsis thaliana root meristem (2006) The Plant Journal, 48, pp. 619-627; Dabov, K., Foi, A., Katkovnik, V., Egiazarian, K., Image denoising by sparse 3d transform-domain collaborative filtering (2007) IEEE Trans. on Image Processing, 16 (8), pp. 2080-2095. , August; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of arabidopsis thaliana root meristem in confocal microscopy (2004) Proc. of the Inter. Conf. on Image Analysis and Recognition, pp. 166-174. , Springer LCNS 3212; Harris, C., Stephens, M., A combined corner and edge detector (1988) Proc. of the 4th Alvey Vision Conf.; Hartley, R., Zisserman, A., (2003) Multiple View Geometry in Computer Vision, , Cambridge University Press; Iwamoto, A., Satoh, D., Furutani, M., Maruyama, S., Ohba, H., Sugiyama, M., Insight into the basis of root growth in arabidopsis thaliana provided by a simple mathematical model (2006) J. Plant Res., 119, pp. 85-93; Luc, V., Soille, P., Watersheds in digital spaces: An efficient algorithm based on immersion simulations (1991) IEEE Trans. on PAMI, 13 (6), pp. 583-598; Marcuzzo, M., Quelhas, P., Campilho, A., Mendonça, A.M., Campilho, A., A hybrid approach for cell image segmentation (2008) Proc. of the ICIAR, pp. 739-749. , Springer LCNS 5112; Meyer, F., Beucher, S., Morphological segmentation (1990) JVCIR, 1 (1), pp. 21-46. , Sept; Mohinder, S., Angus, P., (1993) Kalman Filtering Theory and Practice, , Prentice Hall; Roberts, T., Mckenna, S., Wuyts, N., Valentine, T., Bengough, A., Performance of low-level motion estimation methods for confocal microscopy of plant cells in vivo (2007) Motion07, pp. 13-13
Keywords: Arabidopsis thaliana; Bioinformatics; Cell tracking; confocal microscopy; Image acquisition; Image data; In-vivo; Individual cells; Motion estimation; Pattern recognition; Point correspondence; Root cells; Structured information; Time-lapse microscopy; Tracking system; Two stage

Watershed framework to region-based image segmentation - Monteiro, F.C.; Campilho, A. (Proceedings - International Conference on Pattern RecognitionProc. Int. Conf. Pattern Recognit., 2008)
This paper proposes a new framework to image segmentation which combines edge- and region-based information with spectral techniques through the morphological algorithm of watersheds. A pre-processing step is used to reduce the spatial resolution without losing important image information. An initial partitioning of the image into primitive regions is set by applying a rainfalling watershed algorithm on the image gradient magnitude. This initial partition is the input to a computationally efficient region segmentation process which produces the final segmentation. The latter process uses a region-based similarity graph representation of the image regions. The experimental results clearly demonstrate the effectiveness of the proposed approach to produce simpler segmentations and to compare favourably with state-of-the-art methods. © 2008 IEEE.
Conference code: 81859Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 4761587CODEN: PICRELanguage of Original Document: EnglishCorrespondence Address: Monteiro, F. C.; INEB - Instituto de Engenharia BiomédicaPortugal; email: monteiro@ipb.ptReferences: Callaghan, R.O., Bull, D., Combined morphologicalspectral unsupervised image segmentation (2005) IEEE Transactions on Image Processing, 14 (1), pp. 49-62;Comaniciu, D., Meer, P., Mean shift: A robust approach toward feature space analysis (2002) IEEE Trans. Pattern Analysis and Machine Intelligence, 24 (5), pp. 603-619; Cour, T., Benezit, F., Shi, J., Spectral segmentation with multiscale graph decomposition (2005) Proc. of IEEE Int. Conf. on Computer Vision and Pattern Recognition, 2, pp. 1124-1131. , June; De Bock, J., De Smet, P., Philips, W., Image segmentation using watersheds and normalized cuts (2005) Proceedings of SPIE - The International Society for Optical Engineering, 5675, pp. 164-173. , Imaging - Vision Geometry XIII; Deng, Y., Manjunath, B., Unsupervised segmentation of color-texture regions in images and video (2001) IEEE Transactions on Pattern Analysis and Machine Intelligence, 23 (8), pp. 800-810; Martin, D., Fowlkes, C., Tal, D., Malik, J., A database of human segmented natural images and its application to evaluating segmentation algorithms and measuring ecological statistics (2001) Proc. of IEEE Int. Conference on Computer Vision, 2, pp. 416-423. , http://www.cs.berkeley.edu/projects/vision/grouping/segbench/, online at; Monteiro, F., (2007) Region-based Spatial and Temporal Image Segmentation, , PhD thesis, Faculdade de Engenharia da Universidade do Porto, Portugal
Keywords: Computationally efficient; Edge detection; Graph representation; Image gradients; Image information; Image regions; Image segmentation; Landforms; Pre-processing step; Process use; Rainfalling watershed; Region segmentation; Region-based; Spatial resolution; Spectral techniques; State-of-the-art methods; Watersheds

Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation - Amaral, I.F.; Cordeiro, A.L.; Sampaio, P.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2007)
Chitosan (Ch) is being actively investigated as a non-protein template for the growth of an increasing number of anchorage-dependent cells, including chondrocytes and bone cells. In the present work, Ch films with degrees of N-acetylation (DAs) in the range of 4 to 49% were evaluated with respect to the attachment, spreading and short-term proliferation of osteoblasts, using human osteoblastic MG-63 cells. The films were characterized in terms of surface morphology and surface charge by atomic force microscopy and streaming potential measurements, respectively. Cell attachment was assessed after 3 and 24 h of cell culture. After 24 h of incubation, cell attachment was found to be dependent on the DA, lower DAs favouring cell adhesion. With time, cell spreading and cytoskeleton organization were only attained for DAs ≤ 13%. Regarding cell proliferation, cells grown on films with the lowest DA (4%) revealed a higher specific growth rate as compared to those grown on films with higher DAs. Films with a DA of 49% failed to sustain cell proliferation. In addition, a longer lag-phase was observed on Ch, as compared to TCPS, in accordance to an observed delay of cell spreading. The present findings revealed that differences in the DA as small as 9% may be critical in terms of the osteoblast response to two-dimensional Ch-based matrices. © 2007 VSP.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856207780425068Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; Biocompatible Materials; Chitosan, 9012-76-4References: Vacanti, C.A., Bonassar, L.J., Vacanti, J.P., (2000) Principles of Tissue Engineering, p. 671. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA;Bruder, S.P., Caplan, A.I., (2000) Principles of Tissue Engineering, p. 683. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA; Burg, K.J.L., Porter, S., Kellam, J.F., (2000) Biomaterials, 21, p. 2347; Khor, E., Lim, L.Y., (2003) Biomaterials, 24, p. 2339; Nettles, D.L., Elder, S.H., Gilbert, J.A., (2002) Tissue Eng, 8, p. 1009; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J. Control. Rel, 78, p. 187; Muzzarelli, R.A.A., (1997) Cell. Mol. Life Sci, 53, p. 131; Madihally, S.V., Matthew, H.W.T., (1999) Biomaterials, 20, p. 1133; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., (2000) Biomaterials, 21, p. 2315; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., (2000) J. Biomed. Mater. Res, 51, p. 586; Ho, M.H., Wang, D.M., Hsieh, H.J., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., (2005) Biomaterials, 26, p. 3197; A. Domard, in: Advances in Chitin Science, II, A. Domard, G. A. F. Roberts and K. M. Varum (Eds), p. 410. Jacques André, Lyon (1997)Tomihata, K., Ikada, Y., (1997) Biomaterials, 18, p. 567; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., (1992) Int. J. Biol. Macromol, 14, p. 166; Anselme, K., (2000) Biomaterials, 21, p. 667; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., (2000) J. Mater. Sci. Mater. Med, 11, p. 773; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Dhiman, H.K., Ray, A.R., Panda, A.K., (2004) Biomaterials, 25, p. 5147; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., (2001) Polymer, 42, p. 3569; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., (1983) J. Appl. Polym. Sci, 28, p. 1909; Aiba, S., (1986) Int. J. Biol. Macromol, 8, p. 173; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., (1996) Carbohydr. Polym, 29, p. 63; (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test as an End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services, Public Health Service, Food and Drug Administration, US Department of Health and Human Services, Washington, DC; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Haishima, Y., (2003) J. Biomed. Mater. Res, 66 B, p. 347; Walker, S.L., Bhattacharjee, S., Hoek, E.M.V., Elimelech, M., (2002) Langmuir, 18, p. 2193; Clover, J., Gowen, M., (1994) Bone, 15, p. 585; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., (2000) Colloid Surfaces B: Biointerfaces, 19, p. 367; Sorlier, P., Denuziere, A., Viton, C., Domard, A., (2001) Biomacromolecules, 2, p. 765; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J. Biomed. Mater. Res, 75 A, p. 387; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) Surface and Interfacial Aspects of Biomedical Polymers, 1, p. 249. , J. D. Andrade Ed, p, Plenum Press, New York, NY; Dewez, J.L., Doren, A., Schneider, Y.J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Kikuchi, T., Yoshikai, Y., Miyoshi, J., Katsuki, M., Musikacharoen, T., Mitani, A., Tanaka, S., Matsuguchi, T., (2003) J. Dent. Res, 82, p. 546; Denuziere, A., Ferrier, D., Damour, O., Domard, A., (1998) Biomaterials, 19, p. 1275; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, p. 485; Wang, J.H., Wei, C.W., Liu, H.C., Young, T.H., (2003) J. Biomed. Mater. Res, 64 A, p. 606; Michael, K.E., Vernekar, V.N., Keselowsky, B.G., Meredith, J.C., Latour, R.A., Garcia, A.J., (2003) Langmuir, 19, p. 8033; Keselowsky, B.G., Collard, D.M., Garcia, A.J., (2003) J. Biomed. Mater. Res, 66 A, p. 247; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., (2003) J. Biomed. Mater. Res, 67 A, p. 538; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., (1999) J. Biomed. Mater. Res, 44, p. 1; Cowles, E.A., Brailey, L.L., Gronowicz, G.A., (2000) J. Biomed. Mater. Res, 52, p. 725; Marco, R.A.W., Diaz-Montero, C.M., Wygant, J.N., Kleinerman, E.S., McIntyre, B.W., (2003) J. Cell. Biochem, 88, p. 1038; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., (1995) J. Biomed. Mater. Res, 29, p. 389; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res, 49, p. 155; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., (2004) Biomaterials, 25, p. 2695
Keywords: Acetylation; AFM; article; Atomic force microscopy; Biocompatible Materials; biofilm; Biofilms; biomaterial; bone cell; cartilage cell; cell adhesion; cell anchorage; Cell culture; cell growth; Cell Line, Tumor; cell proliferation; Cell Shape; cell spreading; cell survival; Chemical structure; chemistry; Chitin; chitosan; comparative study; controlled study; cytoskeleton; Degree of acetylation; drug effect; Growth kinetics; human; human cell; Humans; incubation time; metabolism; Microscopy, Atomic Force; osteoblast; Osteoblast-like cells; Osteoblasts; Pathology; priority journal; Surface charge; Surface Properties; surface property; Surface treatment; tumor cell line; Zeta potential

Automatic vertebra detection in x-ray images - Moura, D.C.; Correia, M.V.; Barbosa, J.G.; Reis, A.M.; Laranjeira, M.; Gomes, E. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
In this paper we will describe our experiments with x-ray image analysis for vertebra detection in juvenile/adolescent patients with idiopathic scoliotic spines. We will focus on detecting vertebrae location in a anterior-posterior x-ray image in a fully automatic way. For accomplishing this, we propose a set of techniques for (i) isolating the spine by removing other bone structures (e.g. ribs), (ii) detecting vertebrae location along the spine using an hierarchical and progressive threshold analysis, and (iii) detecting vertebrae lateral boundaries. © 2007 Taylor & Francis Group.
Conference code: 75470Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Moura, D. C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem, Porto, PortugalReferences: Benameur, S., Mignotte, M., Labelle, H., Guise, J.A.D., A hierarchical statistical modeling approach for the unsupervised 3-d biplanar reconstruction of the scoliotic spine (2005) IEEE Trans Biomed Eng, 52 (12), pp. 2041-2057. , December;de Bruijne, M. and M. Nielsen (2004a). Image segmentation by shape particle filtering, Chapter III, pp. 722-725. International Conference on Pattern Recognition. IEEE Computer Society Pressde Bruijne, M., Nielsen, M., Shape particle filtering for image segmentation (2004) Lecture Notes in Computer Science, 3216, pp. 168-175. , of, Chapter I, pp, Springer; Ghebreab, S., Smeulders, A., Combining strings and necklaces for interactive threedimensional segmentation of spinal images using an integral deformable spine model (2004) IEEE Trans Biomed Eng, 51 (10), pp. 1821-1829. , October; Pomero, V., Mitton, D., Laporte, S., de Guise b, J.A., Skalli, W., Fast accurate stereoradiographic 3d-reconstruction of the spine using a combined geometric and statistic model (2004) Clinical Biomechanics, 19 (3), pp. 240-247. , March; Scott, I., Cootes, T., Taylor, C., Shape particle filtering for image segmentation (2003) Lecture Notes in Computer Science, 2732, pp. 258-269. , of, Springer; Smyth, P., Taylor, C., Adams, J., Vertebral shape: Automatic measurement with active shape models (1999) Radiology, 211 (2), pp. 571-578; Zamora, G., Sari-Sarrafa, H., Long, R., Hierarchical segmentation of vertebrae from x-ray images (2003) Med Imaging: Image Process, 5032, pp. 631-642. , SPIE Press
Keywords: Anterior posteriors; Bone structures; Image analysis; Lateral boundaries; Mammals; Threshold analysis; X ray analysis; X ray apparatus; X-ray images

Characterization of hydroxyapatite sputtered films doped with titanium - Ribeiro, A.R.; Piedade, A.P.; Ribeiro, C.C.; Vieira, M.T.; Barbosa, M.A. (Key Engineering MaterialsKey Eng Mat, 2007)
In the present work, thin films of hydroxyapatite (HAp), titanium, and hydroxyapatite doped with different titanium concentrations were obtained by sputtering and characterized using several analytical techniques. These films are intended to be used as model surfaces on protein adsorption studies in order to better understand the role of titanium ions in biological processes.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Ribeiro, A.R.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Universidade do Porto, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: arr@ineb.up.ptReferences: Bhat, (2002) Biomaterials, , Narosa Publishing House/Kluwer Academic Publishers, India;Feddes B, Vredenberg AM. Wolke JGC, Jansen JA.: Surface and Coatings Technology 185 (2-3) (2004), p. 346Gisep, A., (2002) Injury-International Journal of the Care of the Injured, 33 (SUPPL. 2), p. 88; Ooms, E.M., Wolke, J.G.C., van der Waerden, J.P.C.M., (2002) Journal of Biomedical Materials Research, 61 (1), p. 9; Barrias, C.C., Ribeiro, C.C., Rodriguez, D., Sá Miranda, C., Barbosa, M.A., (2005) Key Engineering Materials, 284-286, p. 689; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., (2004) Biomaterials, 25, p. 4363; van Dijk, K., Schaeken, H.G., Marée, C.H.M., Verhoeven, J., Wolke, J.C.G., Habraken, F.H.P.M., Jansen, J.A., (1995) Surface and Coatings Technology, 76-77, p. 206; Hulshoff, J.E.G., van Dijk, K., de Ruijter, J.E., (1998) Journal of Biomedical Materials Research, 40 (3), p. 464; Yang, Y.Z., Kim, K.H., Ong, J.L., (2005) Biomaterials, 26 (3), p. 327; Ong, J.L., Lucas, L.C., (1998) Biomaterials, 19 (4-5), p. 455; Thian, E.S., Huang, J., Best, S.M., Barber, Z.H., Bonfield, W., (2005) Biomaterials, 26, p. 2947
Keywords: Adsorption; Biofilms; Doping (additives); hydroxyapatite; Hydroxyapatite sputtered films; Model surfaces; Proteins; Sputtering; Titanium; Titanium ions

Degradation studies of some polymeric biomaterials: Polypropylene PP and polyvinylidene difluoride (PVDF) - Silva, R.A.; Silva, P.A.; Carvalho, M.E. (Materials Science ForumMater Sci Forum, 2007)
Degradation studies of PP and PVDF monofilaments were carried out using a special chamber for several periods of time. One set of the samples was exposed to a 0.9 % NaCl solution and to ultraviolet radiation at 83° C and the other set involved the exposition in air under the same conditions of irradiation and temperature. Scanning Electron Microscopy (SEM) analysis showed direct evidence of PP degradation. Meanwhile, the PVDF monofilaments showed no apparent evidence of degradation under the same conditions. Differential Thermal Analysis (DTA) curves, FTIR spectra and Oxidation Induction Time experiments confirmed the results of SEM Analysis.
Conference code: 71122Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Silva, R.A.; Instituto Superior de Engenharia do Porto, Rua Dr. António Bernardino de Almeida, 431, 4200-072 Porto, Portugal; email: rasilva@isep.ipp.ptReferences: Kurosaki, S., Otsuka, H., Kunitomo, M., Koiama, M., Pawankar, R., Matumoto, K., (1999) J. Nippon. Med. Sch, 66, pp. 41-44;Salthouse, T.N., Biocompatibility of Sutures (1982) Biocompatibility in Clinical Practice, 1, pp. 11-33. , D. F. Williams ed, Boca Raton, FL: CRC Press Inc; Craig, P.A., Williams, I.A., Magoun, A.D., Levin, A.J., Bogdansky, S., Jones, J.P., (1975) Surg. Gynecol. Obstet, 141, pp. 1-8; D. F. Williams. Corrosion and Degradation of implant Materials, B. C. Syrett, A. Acharya, eds. STP 684, Philadelphia, PA: ASTM Special Technical Publication, (1978) 61-75Dahlke, H., Docia, N., Thurran, K., (1980) J. Biomed. Mater. Res, 14, pp. 51-68; Postlethwait, R.W., (1975) Ann. Sur, 190, pp. 127-132; Salthouse, T.N., Matlaga, B.F., (1985) J. Surg. Res, 19, pp. 127-132; Alaymo, F., Vacarri, M., (1985) Ann. Thoracic. Surg, 39, pp. 400-404; Cornel, G., (1982) Ann. Thoracic. Surg, 33, pp. 64-67; Kawai, H., (1969) Jpn. J. Appl. Phys, 8, pp. 975-976; Bergman Jr., J.G., Mcfee, J.H., Crane, G.R., (1971) Appl. Phys. Lett, 18, pp. 203-205; Xiao, D.Q., Lang, S.B., (1989) IEEE Trans. Elec. Insul, 24, pp. 503-516; Ganz, B., (1989) IEEE Trans. Elec. Insul, 24, pp. 499-502; Laroche, G., Marois, Y., Guidoin, R., King, M., Martin, L., How, T., Douville, Y., (1995) J. Biomed. Mater. Res, 29, pp. 1525-1536; Ademovic, Z., Klee, D., Kingshott, P., Kaufman, R., Hocker, H., (2002) Biomolecular Engineering, 19, pp. 277-182; Klee, D., Ademovic, Z., Bosserhoff, A., Hocker, H., Maziolis, G., Erli, H.-J., (2003) Biomaterials, 24, pp. 3663-3670; Wada, A., Kubota, H., Hatanaka, H., Miura, H., Iwamoto, Y., (2001) J. Hand Surg, 26 B, pp. 212-216; Klinge, U., Klosterhalfen, B., Hottinger, A.P., Junge, K., Schumpelick, V., (2002) Biomaterials, 23, pp. 3487-3493
Keywords: Biomaterials; Degradation; Degradation of polypropylene and polyvinylidene difiuoride; Fourier transform infrared spectroscopy; FTIR spectroscopy; Monofilament sutures; Monofilaments; Oxidation induction time; Polypropylenes; Redox reactions; Thermal analysis; Thermoanalysis

Detection of lung nodule candidates in chest radiographs - Pereira, C.S.; Fernandes, H.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2007)
This paper presents an automated method for the selection of a set of lung nodule candidates, which is the first stage of a computeraided diagnosis system for the detection of pulmonary nodules. An innovative operator, called sliding band filter (SBF), is used for enhancing the lung field areas. In order to reduce the influence of the blood vessels near the mediastinum, this filtered image is multiplied by a mask that assigns to each lung field point an a priori probability of belonging to a nodule. The result is further processed with a watershed segmentation method that divides each lung field into a set of non-overlapping areas. Suspicious nodule locations are associated with the regions containing the highest regional maximum values. The proposed method, whose result is an ordered set of lung nodule candidate regions, was evaluated on the 247 images of the JSRT database with very promising results. © Springer-Verlag Berlin Heidelberg 2007.
Conference code: 70962Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pereira, C.S.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem, Campus FEUP (Faculdade de Engenharia da Universidade do Porto), Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: cmsp@fe.up.ptReferences: Wei, J., Hagihara, Y., Shimizu, A., Kobatake, H., Optimal image feature set for detecting lung nodules on chest X-ray images (2002) CARS 2002;Keserci, B., Yoshida, H., Computerized detection of pulmonary nodules in chest radiographs based on morphological features and wavelet snake model (2002) Medical Image Analysis, 6, pp. 431-447; Yoshida, H., Local contralateral subtraction based on bilateral symmetry of lung for reduction of false positives in computerized detection of pulmonary nodules, Biomedical Engineering (2004) IEEE Transactions, 51, pp. 778-789; Suzuki, K., Shiraishi, J., Abe, H., MacMahon, H., Doi, K., False-positive reduction in computer-aided diagnostic scheme for detecting nodules in chest radiographs by means of massive training artificial neural network (2005) Academic Radiology, 12, pp. 191-201; Schilham, A., van Ginneken, B., Loog, M., Multi-scale Nodule Detection in Chest Radiographs (2003) LNCS, 2878, pp. 602-609. , Ellis, R.E, Peters, T.M, eds, MICCAI 2003, Springer, Heidelberg; Schilham, A., van Ginneken, B., Loog, M., A computer-aided diagnosis system for detection of lung nodules in chest radiographs with an evaluation on a public database (2006) Medical Image Analysis, 10, pp. 247-258; Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Transactions on Image Processing, 8 (8); Shiraishi, J., Katsuragawa, S., Kezoe, S., Matsumoto, T., Kobayashi, T., Komatsu, K., Matsui, M., Doi, K., Development of a Digital Image Database for Chest Radiographs With and Without a Lung Nodule: Receiver Operating Characteristic Analysis of Radiologists' Detection of Pulmonary Nodules (2000) American Journal of Roentgenology, 174, pp. 71-74; Kobatake, H., Murakami, M., Adaptive filter to detect rounded convex regions: Iris filter (1996) Int. Conf. Pattern Recognition, 11, pp. 340-344; Wei, J., Hagihara, Y., Kobatake, H.: Detection of cancerous tumors on chest X-ray images - Candidate detection filter and its evaluation, ICIP99, no. 27AP4.2 (1999)Kobatake, H., Wei, J., Yoshinaga, Y., Hagihara, Y., Shimizo, A., Nonlinear Adaptine Convergence Index Filters and Their Characteristics (2000) Int. Conf. Pattern Recognition, pp. 522-525
Keywords: Blood Vessels; Computer aided diagnosis; Database systems; Lung nodule candidates; Non-overlapping areas; Pulmonary diseases; Pulmonary nodules; Radiography; Sliding band filter (SBF)

Efficient approximation of the mahalanobis distance for tracking with the Kalman filter - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
We address the problem of tracking efficiently feature points along image sequences. To estimate the undergoing movement we use an approach based on Kalman filtering which performs the prediction and correction of the features movement in every image frame. In this paper measured data is incorporated by optimizing the global correspondence set based on efficient approximations of the Mahalanobis distances (MD). We analyze the difference between using the MD and its efficient approximation in the tracking results, and also examine the related computational costs. Experimental results which validate our approach are presented. © 2007 Taylor & Francis Group.
Conference code: 75470Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pinho, R. R.; FEUP- Faculdade de Engenharia da Universidade do PortoPortugalReferences: Brown, L., Senior, A., Tian, Y., Connell, J., Hampapur, A., Shu, C., Merkl, H., Lu, M., Performance evaluation of surveillance systems under varying conditions (2005) IEEE International Workshop on Performance Evaluation of Tracking and Surveillance, , Colorado, USA;Cucchiara, R., Grana, C., Piccardi, M., Prati, A., Statistic and knowledge-based moving object detection in traffic scenes (2000) IEEE Conference on Intelligent Transportation Systems, , Dearborn, USA; Jorge, P., Abrantes, A., Marques, J., On-line tracking groups of pedestrians with bayesian networks (2004) Workshop PETS, , Prague, Czech Republic; Kato, N., M. Abe, and Y. Nemoto (1996). A handwritten character recognition system using modified mahalanobis distance. Transactions Institute of Electronics, Information and Communication Engineers (IEICE) J79-D{1), 45-52Kimura, F., Shridhar, M., Handwritten numerical recognition based on multiple algorithms (1991) Pattern Recognition, 24, pp. 969-983; Kurita, M., Tsuruoka, S., Yokoi, S., Miyake, Y., Handprinted "kanji" and "hiragana" character recognition using weighting direction index histograms and quasimahalanobis distance. Technical report (1983) IEICE Technical Report, , PRL82-79; Lin, L., Bar-Shalom, Y., New assignment-based data association for tracking move-stop-move targets (2004) IEEE Transactions on Aerospace and Electronic Systems, 40 (2), pp. 714-725; O'Malley, P., Nechyba, M., Arroyo, A., Human activity tracking for wide-area surveillance (2002) 2002 Florida Conference on Recent Advances in Robotics, , Miami, USA; Pinho, R., Tavares, J., Correia, M., Human movement tracking and analysis with kalman filtering and global optimization techniques (2005) II International Conference On Computational Bioengineering, , Lisbon, Portugal; Sun, F., Omachi, S., Kato, N., Aso, H., Kono, S., Takagi, T., Two-stage computational cost reduction algorithm based on mahalanobis distance approximations (2000) International Journal of Pattern Recognition, 2, pp. 2969-2973; Welch, G., Bishop, G., An Introduction to Kalman Filter (1995), Technical report, University of North Carolina at Chapel HillWren, C., Azarbayejani, A., Darell, T., Pentland, A., Pfinder: Real-time tracking of the human body (1997) IEEE Transactions on Pattern Analysis and Machine Intelligence, 19 (1), pp. 780-785
Keywords: Computational costs; Control theory; Feature points; Image frames; Image sequences; Kalman filters; Kalman-filtering; Mahalanobis distances; Measured datum

Efficient approximation of the mahalanobis distance for tracking with the Kalman filter - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (International Journal of Simulation ModellingInt. J. Simul. Model., 2007)
In this paper, we address the problem of tracking feature points along image sequences efficiently. Thus, to estimate the undergoing movement we use an approach based on Kalman filtering, which performs the prediction and correction of the features' movement in every image frame. Measured data is incorporated by optimizing the global association set built on efficient approximations of the Mahalanobis distance (MD). We analyze the difference between the usage in the tracking results of the original MD formulation and its more efficient approximation, as well as the related computational costs. Experimental results which validate our approach are presented.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.2507/IJSIMM06(2)S.03Language of Original Document: EnglishCorrespondence Address: Pinho, R.R.; FEUP - Faculdade de Engenharia da Universidade do Porto, INEGI - Instituto de Engenharia. Mecânica e Gestão Industrial, LOMe - Lab. de Óptica e Mecånica ExperimentalPortugal; email: rpinho@fe.up.ptReferences: Wren, C., Azarbayejani, A., Darrell, T., Pentland, A., Pfinder: Real-Time Tracking of the Human Body (1997) IEEE Transactions on Pattern Analysis and Machine Intelligence, 19 (7), pp. 780-785;Cucchiara, R., Grana, C., Piccardi, M., Prati, A., Statistic and Knowledge-based Moving Object Detection in Traffic Scenes (2000) Proceedings of the 3rd IEEE Conference on Intelligent Transportation Systems (ITSC2000), , Dearborn, Indiana, USA; Jorge, P., Abrantes, A., Marques, J., On-line Tracking Groups of Pedestrians with Bayesian Networks (2004) Workshop PETS, , Prague, Czech Republic; Lin, L., Bar-Shalom, Y., New Assignment-Based Data Association for Tracking Move-Stop-Move Targets (2004) IEEE Transactions on Aerospace and Electronic Systems, 40 (2), pp. 714-725; O'Malley, P., Nechyba, M., Arroyo, A., Human Activity Tracking for Wide-Area Surveillance (2002) 2002 Florida Conference on Recent Advances in Robotics, , Miami, USA; Kurita, M., Tsuruoka, S., Yokoi, S., Miyaké, Y., Handprinted "Kanji" and "Hiragana" character recognition using weighting direction index histograms and quasi-Mahalanobis distance (1983) IEICE Technical Report, , PRL82-79; Kato, N., Abe, M., Nemoto, Y., A Handwritten Character Recognition System Using Modified Mahalanobis Distance (1996) Transactions Institute of Electronics, Information and Communication Engineers (IEICE), J79-D (L), pp. 45-52; Kimura, F., Shridhar, M., Handwritten numerical recognition based on multiple algorithms (1991) Pattern Recognition, 24 (10), pp. 969-983; Sun, F., Omachi, S., Kato, N., Aso, H., Kono, S., Takagi, T., Two-Stage Computational Cost Reduction Algorithm Based on Mahalanobis Distance Approximations (2000) International Conference of Pattern Recognition, , Barcelona, Spain; Pinho, R., Tavares, J., Correia, M., Human Movement Tracking and Analysis with Kalman Filtering and Global Optimization Techniques (2005) II International Conference On Computational Bioengineering, , Lisbon, Portugal; Welch, G., Bishop, G., An Introduction to Kalman Filter (1995), University of North Carolina at Chapel Hill, Technical Report, TR 95-041Pinho, R., Tavares, J., Correia, M., A Movement Tracking Management Model with Kaiman Filtering, Global Optimization Techniques and Mahalanobis Distance (2005) ICCMSE 2005 International Conf. on Computational Methods in Science and Engineering, , Loutraki, Greece; Pinho, R., Tavares, J., Correia, M., An Improved Management Model for Tracking Missing Features in Computer Vision Long Image Sequences (2007) WSEAS Transactions on Information Science and Applications, 4 (1), pp. 196-203; Brown, L., Senior, A.W., Tian, Y., Connell, J., Hampapur, A., Shu, C., Merkl, H., Lu, M., Performance Evaluation of Surveillance Systems Under Varying Conditions (2005) IEEE Int. Workshop on Performance Evaluation of Tracking and Surveillance, , Colorado, USA
Keywords: Computational vision; Data association; Kalman filter; Mahalanobis distance; Tracking

Epidemiology of femur fractures in Portugal - Alves, S.F.; Pina, M.D.F.; Barbosa, M. (Epidemiologia das fracturas do fémur em Portugal: Fracturas do colo do fémur versus fracturas de outras localizações não especificadas do fémurArquivos de MedicinaArq. Med., 2007)
Fractures related to osteoporosis have been increasing in many countries. Femoral neck fractures have been widely studied, however little is known about other femur fractures and its relationship with osteoporosis. The main objective of this study is the comparison between the incidence of neck fractures attributed to osteoporosis with the ones that occurs in other places of femur other than the neck, in the same conditions. It was used a national database, under the regulation of a governmental institute, with registers from 2000 to 2002. From the total number of femural fractures the authors selected the registers corresponding to individuals with more than fifty years of age and due to low impact, it were analysed separately the femoral neck fractures (International Classification of Diseases codes, 9 th Revision, Clinical Modification, ICD9-CM codes 820 and derivates) from the fractures that occurred in other locations in the femur (ICD9-CM codes 821 and derivates). Case fatality rates and the incidence rates were calculated for that period of time, and an analysis of the variables age, days and costs of hospital admission as well as of the variable destination after discharge. Only 7.6% of the femural fractures were coded as 821.x, all the others were coded as 820.x. In both groups the fractures were more frequent in women (above 75%) and showed an exponential increase with age. The costs were higher in the 820.x fractures which also presented higher case fatality rates. ©ArquiMed, 2007.
Keywords: adult; aged; article; Female; femur; femur fracture; fracture; hip fracture; human; incidence; Low impact; male; Osteoporosis; outcome assessment; Portugal; risk assessment; survival

Evaluation of contrast enhancement filters for lung nodule detection - Pereira, C.S.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2007)
The aim of this paper is to evaluate and compare the performance of three convergence index (CI) filters when applied to the enhancement of chest radiographs, aiming at the detection of lung nodules. One of these filters, the sliding band filter (SBF), is the proposal of an innovative operator, while the other two CI class members, the iris filter (IF) and the adaptive ring filter (ARF), are already known in this application. To demonstrate the adequacy of the new filter for the enhancement of chest x-ray images, we calculated several figures of merit with the goal of comparing (i) the contrast enhancement capability of the filters, and (ii) the behavior of the filters for the detection of lung nodules. The results obtained for 154 images with nodules of the JSRT database show that the SBF outperforms both the IF and ARF. The proposed filter demonstrated to be a promising enhancement method, thus justifying its use in the first stage of a computer-aided diagnosis system for the detection of lung nodules. © Springer-Verlag Berlin Heidelberg 2007.
Conference code: 70855Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pereira, C.S.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem, Campus FEUP (Faculdade de Engenharia da Universidade do Porto), Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: cmsp@fe.up.ptReferences: Kobatake, H., Murakami, M., Adaptive filter to detect rounded convex regions: Iris filter (1996) Int. Conf. Pattern Recognition, 2, pp. 340-344;Kobatake, H., Hashimoto, S., Convergence index filter for vector fields (1999) IEEE Transactions on Image Processing, 8 (8); Wei, J., Hagihara, Y., Kobatake, H.: Detection of cancerous tumors on chest X-ray images - Candidate detection filter and its evaluation. In: ICIP99, 27AP4.2 (1999)Kobatake, H., Wei, J., Yoshinaga, Y., Hagihara, Y., Shimizo, A., Nonlinear Adaptinc Convergence Index Filters and Their Characteristics (2000) Int. Conf. Pattern Recognition, pp. 522-525; Shiraishi, J., Katsuragawa, S., Kezoe, S., Matsumoto, T., Kobayashi, T., Komatsu, K., Matsui, M., Doi, K., Development of a Digital Image Database for Chest Radiographs With and Without a Lung Nodule: Receiver Operating Characteristic Analysis of Radiologists' Detection of Pulmonary Nodules (2000) American Journal of Roentgenology, 174, pp. 71-74; Keserci, B., Yoshida, H., Computerized detection of pulmonary nodules in chest radiographs based on morphological features and wavelet snake model (2002) Medical Image Analysis, 6, pp. 431-447; Song, X., Pogue, B., Jiang, S., Doyley, M., Dehghani, H., Tosteson, T., Paulsen, K., Automated region detection based on the contrast-to-noise ratio in near-infrared tomography (2004) Applied Optics, 43 (5), pp. 1053-1062; Singh, S., Bovis, K., An evaluation of contrast enhancement techniques for mammographic breast masses (2005) IEEE Transactions On Information Technology in Biomedicine, 9 (1), pp. 109-119; Wei, J., Hagihara, Y., Shimizu, A., Kobatake, H., Optimal image feature set for detecting lung nodules on chest X-ray images (2002) CARS; Suzuki, K., Shiraishi, J., Abe, H., MacMahon, H., Doi, K., False-positive reduction in computer-aided diagnostic scheme for detecting nodules in chest radiographs by means of massive training artificial neural network (2005) Academic Radiology, 12, pp. 191-201;
Keywords: Adaptive systems; Contrast enhancement filters; Database systems; Image segmentation; Iris filter (IF); Medical imaging; Radiography; X rays

Face detection based on skin color in video images with dynamic background - Ferreira, A.M.; Correia, M.V. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2007)
Face detection is a problem in image processing that has been extensively studied in the last decades. This fact is justified due to the innumerous applications this subject has in computer vision. In this paper we present a technique to detect a face in an image where several persons may be. The images were recorded from news broadcasts from different networks. First, a model based on normalized RGB color space was built to define a skin color model: skin regions were selected from several face images and extracted statistical characteristics. Second, each pixel of the image was classified in two categories: skin and not skin. Third, the face region was identified. A MATLAB function was created to detect faces of any size, achieving high detection rates. © Springer-Verlag Berlin Heidelberg 2007.
Conference code: 70855Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Ferreira, A.M.; Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem, Departamento de Engenharia Electrotécnica e de Computadores, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: mota.ferreira@fe.up.ptReferences: Chelllappa, R., Wilson, C., Sirohey, S., Human and machine recognition of faces: A survey (1995) IEEE, 83, pp. 705-740;Viola, P., Jones, M., Robust Real-Time Face Detection (2004) International Journal of Computer Vision, 57 (2), pp. 137-154; Schneiderman, H., Kanade, T., A Statistical Method for 3D Object Detection Applied to Faces and Cars (2000) IEEE Conference on Computer Vision and Pattern Recognition, June, , IEEE Computer Society Press, Los Alamitos; Rowley, H., Baluja, S., Kanade, T., (1995) Human face detection in visual scenes, , November; Vazhnevets, V., Sazonov, V., Andreeva, A., A Survey on Pixel-Based Skin Color Detection Techniques (2003) Proceedings Graphicon-2003, pp. 85-92. , Moscow, Russia, September; Crowley, J.L., Berard, F., Multimodel Tracking of Faces for Video Communications (1997) IEEE Proc. Conference on Computer Vision and Pattern Recognition, pp. 640-645. , IEEE Computer Society Press, Los Alamitos; Garcia, C., Zikos, G., Tziritas, G., Face detection in Color Images Using Wavelet Packet Analisis (1999) ICMCS, 1, pp. 703-708
Keywords: Color; Color segmentation; Computer vision; Face detection; Face recognition; MATLAB; Skin; Skin color model; Skin detection

A Gait Analysis Laboratory for rehabilitation of patients with musculoskeletal impairments - Sousa, D.S.S.; Tavares, J.M.R.S.; Correia, M.V.; Barbosa, J.G.; Chã, C.V.; Mendes, E. (Proceedings of the International Symposium CompIMAGE 2006 - Computational Modelling of Objects Represented in Images: Fundamentals, Methods and ApplicationsProc. Int. Symp. CompIMAGE - Comput. Model. Objects Represent. Images: Fundam., Methods Appl., 2007)
This paper describes the technology (software & hardware) used in the Gait Analysis Laboratory of CRPG - Centro de Reabilitação Projissional de Gaia. This laboratory is mainly intended to support CRPG with quantitative data for clinical rehabilitation of patients with musculoskeletal pathologies, namely in the lower limbs. Usually, for the gait analysis is considered data obtained from several acquisition sensors, such as: image cameras, electromyographic devices, pressure devices and force plates. This paper also presents briefly how quantitative motion analysis can be used for a clinical point of view and it presents the influence of image algorithms in gait rehabilitation. © 2007 Taylor & Francis Group.
Conference code: 75470Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, D. S. S.; INEGI, Instituto de Engenharia Mecǎnica e Gestão Industrial, Porto, PortugalReferences: Baker, R., Gait analysis methods in rehabilitation (2006) Journal of Neuro Engineering and Rehabilitation, 3 (1), p. 4;Cappozzo, A., Delia Croce, U., Human movement analysis using stereophotogrammetry. Part I: Theoretical background (2005) Gait & Posture, 21, pp. 186-196; Chau, T., A review of analytical techniques for gait data. Part 1: Fuzzy, statistical and fractal methods (2001) Gait & Posture, 13 (1), pp. 49-66; Davis, R.B., Reflections on clinical gait analysis (1997) Journal of Electromyography and Kinesiology, 7 (4), pp. 251-257; Davis III, R.B., Clinical gait analysis (1988) Engineering in Medicine and Biology Magazine, IEEE, 7 (3), pp. 35-40; Figueroa, P.J., Leite, N.J., A flexible software for tracking of markers used in human motion analysis (2003) Computer Methods and Programs in Biomedicine, 72, pp. 155-165; Gavrila, D., The visual analysis of human movement: A survey (1999) Computer Vision and Image Understanding, 73 (1), pp. 82-98; Merletti, R., Parker, P., (2004) Electromyography: Physiology, engineering and noninvasive applications, , Wiley-IEEE Press; (1978) NASA Reference Publication, , NASA, Springfield: NASA; Orlin, M., McPoil, T., Plantar pressure assessment (2000) Physical therapy, 80 (4), pp. 399-409; Perry, J., The contribution of dynamic electromyography to gait analysis (1998) Monograph 002: Gait analysis in the science of rehabilitation. 1998, , J. DeLisa ed, Washington, DC; Pinho, R., Tavares, J., A Movement Tracking Management Model with Kalman Filtering, Global Optimization Techniques and Mahalanobis Distance (2005) ICCMSE 2005 - International Conference of Computational Methods in Sciences and Engineering; Loutraki, 21-26 October 2005, , Korinthos: Greece; Pinho, R., Tavares, J., Human Movement Tracking and Analysis with Kalman Filtering and Global Optimization Techniques (2005) ICCB2005 - II International Conference on Computational Bioengineering; Instituto Superior Técnico, Lisboa, 14-16 September 2005, , Lisboa: Portugal; Rosenbaum, D., Becker, H., Plantar pressure distribution measurements. Technical background and clinical applications (1997) Foot and Ankle Surgery, 3 (1), pp. 1-14; Roy, K., Force, pressure and motion measurements in the foot: Current concepts (1988) Clinics in Podiatric Medicine and Surgery, 5, pp. 491-508; Schmalz, T., Blumentrit, S., Energy expenditure and biomechanical characteristics of lower limb amputee gait: The influence of prosthetic alignment and different prosthetic components (2002) Gait & Posture, 16, pp. 255-263; Shabana, A., (2001) Computational Dynamics, , NY: John Wiley; Sisto, S. 1998. An overview of the value of information resulting from instrumented gait analysis for the physical therapist. In J. DeLisa (ed.) Monograph 002: Gait analysis in the science of rehabilitation. 1998. Washington, DC. Sutherland, D. 2001. The evolution of clinical gait analysis part 1: kinesiological EMG. Gait & Posture 14(1): 61-70Sutherland, D., The evolution of clinical gait analysis: Part II Kinematics (2002) Gait & Posture, 16 (2), pp. 159-179; Tavares, J., Bastos, L., Improvement of Modal Matching Image Objects in Dynamic Pedobarography using Optimization Techniques (2005) Electronic Letters on Computer Vision and Image Analysis, special issue on Articuled Motion & Deformable Objects, 5, pp. 1-20; Tavares, J., Barbosa, J., Matching Image Objects in Dynamic Pedobarography (2000) RecPad 2000 - 11th Portuguese Conference on Pattern Recognition; Porto, 11-12 Maio 2000, , Porto, Portugal; Urry, S., Plantar pressure-measurement sensors (1999) Measurement Science and Technology, 10, pp. 16-32; Whittle, M., Clinical gait analysis: A review (1996) Human Movement Science, 15, pp. 369-387; Whittle, M., (2003) Gait analysis an introduction, , Oxford, Boston: Butterworth-Heinemann; Winter, D., (2005) Biomechanics and motor control of human movement, , Hoboken: John Wiley & Sons
Keywords: Acquisition sensors; Electromyographic; Force plates; Gait analysis; Gait rehabilitations; Image algorithms; Lower limbs; Motion analysis; Patient rehabilitation; Pressure devices; Quantitative datum

An improved management model for tracking missing features in computer vision long image sequences - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (WSEAS Transactions on Information Science and ApplicationsWSEAS Trans. Inf. Sci. Appl., 2007)
In this paper we present a management model to deal with the problem of tracking missing features during long image sequences using Computational Vision. Some usual difficulties related with missing features are that they may be temporarily occluded or might even have disappeared definitively, and the computational cost involved should always be reduced to the strictly necessary. The proposed Net Present Value (NPV) model, based on the economic Theory of Capital, considers the tracking of each missing feature as an investment. Thus, using the NPV criterion, with adequate receipt and outlay functions, each occluded feature may be kept on tracking or it may be excluded of the tracking process depending on its historical behavior. This approach may be applied to any tracking system as long as the tracking results may be evaluated in each temporal step, and it can deal with the appearance, occlusion and disappearance of features especially useful for tracking in long image sequences. Experimental results, both on synthetic and real image sequences, which validate our model, will be also presented.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pinho, R.R.; FEUP - Faculdade de Engenharia da Universidade do Porto, INEGI - Instituto de Engenharia Mecânica e Gestão Industrial, LOME - Lab. de Óptica e Mecânica Experimental, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: rpinho@fe.up.ptReferences: Davison, A., Deutscher, J., Reid, I., "Markerless motion Capture of Complex Full-Body Movement for Character Animation" (2001) Proceedings Eurographics Workshop on Animation and Simulation, , Manchester, UK;Lakany, H., Hayes, G., Hazlewood, M., Hillman, S., "Human Walking: Tracking and Analysis" (1999) IEEE Electronic & Communications, Colloquium on Motion Analysis and Tracking; Rosales, R., Sclaroff, S., "Improved Tracking of Multiple Humans with Trajectory Prediction and Occlusion Modelling" (1998) Proceedings IEEE Conference on Computer Vision and Pattern Recognition, Workshop on the Interpretation of Visual Motion, , Santa Barbara, USA; Huang, Y., Essa, I., "Tracking Multiple Objects through Occlusions" (2005) IEEE Conference on Computer Vision and Pattern Recognition 2005 (CVPR 2005), , San Diego, USA; Zhao, T.S., Nevatia, R., "Tracking Multiple Humans in Complex Situations" (2004) IEEE Transactions on Image Processing, 26 (9), pp. 1208-1221; Plänkers, R., Fua, P., "Tracking and Modeling People in Video Sequences" (2001) Computer Vision and Image Understanding, 81 (3), pp. 285-302; Jorge, P., Abrantes, A., Marques, J., "On-line Tracking Groups of Pedestrians with Bayesian Networks" (2004) Workshop PETS, , Prague, Czech Republic; Wren, C., Azarbayejani, A., Darrell, T., Pentland, A., "Pfinder: Real-Time Tracking of the Human Body" (1997) IEEE Transactions on Pattern Analysis and Machine Intelligence, 19 (7), pp. 780-785; Tavares, J., Padilha, A., "Matching Lines in Image Sequences with Geometric Constraints" (1995) 7° Congresso Português De Reconhecimento De Padrões, , Aveiro, Portugal; Pinho, R., Tavares, J., Correia, M., "A Movement Tracking Management Model with Kalman Filtering, Global Optimization Techniques and Mahalanobis Distance" (2005) ICCMSE 2005 - International Conference on Computational Methods in Science and Engineering, , Loutraki, Greece; Baumol, W., (1985) Economic Theory and Operations Research, , Prentice-Hall; Levy, H., (1994) Capital Investment and Financial Decisions, , Prentice-Hall; Pinho, R., Tavares, J., Correia, M., "Human Movement Tracking and Analysis with Kalman Filtering and Global Optimization Techniques" (2005) II International Conference On Computational Bioengineering, , Lisbon, Portugal;
Keywords: Automatic target recognition; Computer vision; Feature extraction; Long image sequences; Management; Mathematical models; Missing features; Motion estimation; Net Present Value (NPV); Occlusion; Tracking

Laser surface treatment of hydroxyapatite for enhanced tissue integration: Surface characterization and osteoblastic interaction studies - Teixeira, S.; Monteiro, F.J.; Ferraz, M.P.; Vilar, R.; Eugénio, S. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2007)
Biocompatibility has long been associated with surface microtopography, microtexture, and microchemistry. The surface topography eventually affects the nature and the intensity of the interactions that occur at biomaterial- biological interface (cell adhesion, mobility, spreading, and proliferation). Therefore, it is necessary to produce and work with controlled microtopographical surfaces that present reproducible microdomains of a dimension similar to that of the biological elements of interest (in this case, osteoblasts). There are a number of substrates that already have been studied in terms of surface topography; however, few studies are related to hydroxyapatite (HA) substrates. As it is well established, HA is a well-known ceramic that is extremely used in medical applications, namely implants and coatings. In this work, the surface topography of dense HA substrates was altered by using KFr excimer laser. The surface was characterized by atomic force microscopy and contact angle measurements, while the cell distribution and morphology was assessed by scanning electron microscopy and confocal laser scanning microscopy. Results revealed that the surface is characterized by a homogeneous columnar structure with high specific area. Moreover, cells were able to attach and spread on the surface of the samples, and gradually grow into nearly confluent monolayers. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31073PubMed ID: 17252543Language of Original Document: EnglishCorrespondence Address: Teixeira, S.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: smsilva@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Ceramics; Durapatite, 1306-06-5Manufacturers: Plasma BiotalReferences: Teixeira S, Queiroz AC, Monteiro FJ, Ferraz MP, Vilar R, Eugenio S. Osteoblast proliferation and morphology analysis on laser modified hydroxyapatite surfaces: Preliminary results. Bioceramics 2006;18 (Parts 1, 2):309-311, 105-108Fernandez-Pradas, J.M., Cleries, L., Martinez, E., Sardin, G., Esteve, J., Morenza, J.L., Influence of thickness on the properties of hydroxyapatite coatings deposited by KrF laser ablation (2001) Biomaterials, 22, pp. 2171-2175;Fernandez-Pradas, J.M., Cleries, L., Serra, P., Sardin, G., Morenza, J.L., Evolution of the deposition rate during pulsed laser deposition of hydroxyapatite coatings and its relation with target morphology (2001) Appl Phys A: Mater Sci Process, 72, pp. 613-618; Foltyn, S.R., Dye, R., Ott, K.C., Peterson, E., Hubbard, K.M., Hutchinson, W., Muenchausen, R.E., Wu, X.D., Target modification in the excimer laser deposition of YBa 2Cu 3O 7-x thin films (1991) Appl Phys Lett, 59, pp. 594-596; Khor, K.A., Vreeling, A., Dong, Z.L., Cheang, P., Laser treatment of plasma sprayed HA coatings (1999) Mater Sci Eng A: Struct Mater Prop Microstruct Process, 266 (1-2), pp. 1-7; Ricci, J.L., Alexander, H., Laser microtexturing of implant surfaces for enhanced tissue integration (2001) Key Engineering Mater, pp. 198-199,179-202; Galli, C., Guizzardi, S., Passeri, G., Martini, D., Tinti, A., Mauro, G., Macaluso, G.M., Comparison of human mandibular osteoblasts grown on two commercially available titanium implant surfaces (2005) J Periodontol, 76, pp. 364-372; Oliveira, V., Conde, O., Vilar, R., UV laser micromachining of ceramic materials: Formation of columnar topographies (2001) Adv Eng Mater, 3 (1-2), pp. 75-81; Serra, P., FernandezPradas, J., Sardin, G., Morenza, J.L., Interaction effects of an excimer laser beam with hydroxyapatite targets (1997) Appl Surf Sci, 110, pp. 384-388; Serra, P., Morenza, J.L., Fluence dependence of hydroxyapatite laser ablation plumes (1998) Thin Solid Films, 335 (1-2), pp. 43-48; Duncan, A.C., Weisbuch, F., Rouais, F., Lazare, S., Baquey, C., Laser microfabricated model surfaces for controlled cell growth (2002) Biosens Bioelectron, 17, pp. 413-426; Walboomers, X.F., Croes, H.J.E., Ginsel, L.A., Jansen, J.A., Contact guidance of rat fibroblasts on various implant materials (1999) J Biomed Mater Res, 47, pp. 204-212; Carvalho, P., Manzanares, M.C., Franch, J., Belmonte, A.M., Lafuente, M.P., Serra, I., Fernandez-Pradas, J.M., Morenza, J.L., Osteointegration of calcium phosphate coatings obtained by pulsed laser deposition (2003) J Dent Res, 82, p. 573; Ahmad, M., McCarthy, M., Gronowicz, G., An in vitro model for mineralization of human osteoblast-like cells on implant materials (1999) Biomaterials, 20, pp. 211-220; Matsuura, T., Hosokawa, R., Okamoto, K., Kimoto, T., Akagawa, Y., Diverse mechanisms of osteoblast spreading on hydroxyapatite and titanium (2000) Biomaterials, 21, pp. 1121-1127; Torricelli, P., Fini, M., Giavaresi, G., Borsari, V., Carpi, A., Nicolini, A., Giardino, R., Comparative interspecies investigation on osteoblast cultures: Data on cell viability and synthetic activity (2003) Biomed Pharmacother, 57, pp. 57-62; Boyan, B.D., Lossdoerfer, S., Wang, L., Zhao, G., Lohmann, C.H., Cochran, D.L., Schwartz, Z., Osteoblasts generate an osteogenic microenvironment when grown on surfaces with rough microtopographies (2003) Eur Cell Mater, 6, pp. 22-27; Anselme, K., Bigerelle, M., Topography effects of pure titanium substrates on human osteoblast long-term adhesion (2005) Acta Biomater, 1, pp. 211-222; Anselme, K., Linez, P., Bigerelle, M., Le Maguer, D., Le Maguer, A., Hardouin, P., Hildebrand, H.F., Leroy, J.M., The relative influence of the topography and chemistry of TiAl 6V 4 surfaces on osteoblastic cell behaviour (2000) Biomaterials, 21, pp. 1567-1577; Anselme, K., Noel, B., Hardouin, P., Human osteoblast adhesion on titanium alloy, stainless steel, glass and plastic substrates with same surface topography (1999) J Mater Sci: Mater Med, 10, pp. 815-819; Cleries L, Fernandez-Pradas JM, Morenza JL. Bone growth on and resorption of calcium phosphate coatings obtained by pulsed laser deposition. J Biomed Mater Res 2000;49:43. Erratum 2001;57:473Deligianni, D.D., Katsala, N., Ladas, S., Sotiropoulou, D., Amedee, J., Missirlis, Y.F., Effect of surface roughness of the titanium alloy Ti-6Al-4V on human bone marrow cell response and on protein adsorption (2001) Biomaterials, 22, pp. 1241-1251; dos Santos, E.A., Farina, M., Soares, G.A., Specific proliferation rates of human osteoblasts on calcium phosphate surfaces with variable concentrations of α-TCP (2007) Mater Sci Eng, 27, pp. 61-66; Hao, L., Lawrence, J., Laser surface treatment of magnesia partially stabilized zirconia for enhanced human skin fibroblast cell response (2004) J Laser Appl, 16, pp. 55-64; Kieswetter, K., Schwartz, Z., Dean, D.D., Boyan, B.D., The role of implant surface characteristics in the healing of bone (1996) Crit Rev Oral Biol Med, 7, pp. 329-345; Saldaña, L., Gonzńlez-Carrasco, J.L., Rodriguez, M., Munuera, L., Vilaboa, N., Osteoblast response to plasma-spray porous Ti 6AL 4V coating on substrates of identical alloy (2006) J Biomed Mater Res A, 77, pp. 608-617; Lincks, J., Boyan, B.D., Blanchard, C.R., Lohmann, C.H., Liu, Y., Cochran, D.L., Dean, D.D., Schwartz, Z., Response of MG63 osteoblast-like cells to titanium and titanium alloy is dependent on surface roughness and composition (1998) Biomaterials, 19, pp. 2219-2232; Martin, J.Y., Dean, D.D., Cochran, D.L., Simpson, J., Boyan, B.D., Schwartz, Z., Proliferation, differentiation, and protein synthesis of human osteoblast-like cells (MG63) cultured on previously used titanium surfaces (1996) Clin Oral Implants Res, 7, pp. 27-37; Noth, U., Hendrich, C., Merklein, F., Altvater, T., Rader, C.P., Schutze, N., Eulert, J., Thull, R., Standardised testing of bone-implant surfaces using an osteoblast cell culture system. II. Titanium surfaces of varying degrees of roughness (1999) Biomedizinische Technik, 44 (1-2), pp. 6-11; Ponsonnet, L., Reybier, K., Jaffrezic, N., Comte, V., Lagneau, C., Lissac, M., Martelet, C., Relationship between surface properties (roughness, wettability) of titanium and titanium alloys and cell behaviour (2003) Mater Sci Eng C: Biomimetic Supramolecular Syst, 23, pp. 551-560; Ramires, P.A., Romito, A., Cosentino, F., Milella, E., The influence of titania/hydroxyapatite composite coatings on in vitro osteoblasts behaviour (2001) Biomaterials, 22, pp. 1467-1474; Redey, S.A., Nardin, M., Bernache-Assolant, D., Rey, C., Delannoy, P., Sedel, L., Marie, P.J., Behavior of human osteoblastic cells on stoichiometric hydroxyapatite and type A carbonate apatite: Role of surface energy (2000) J Biomed Mater Res, 50, pp. 353-364; Rosa, A.L., Beloti, M.M., van Noort, R., Osteoblastic differentiation of cultured rat bone marrow cells on hydroxyapatite with different surface topography (2003) Dent Mater, 19, pp. 768-772; Schmidt, C., Ignatius, A.A., Claes, L.E., Proliferation and differentiation parameters of human osteoblasts on titanium and steel surfaces (2001) J Biomed Mater Res, 54, pp. 209-215; Schwartz, Z., Kieswetter, K., Dean, D.D., Boyan, B.D., Underlying mechanisms at the bone-surface interface during regeneration (1997) J Periodontal Res, 32, pp. 166-171; Schwartz, Z., Martin, J.Y., Dean, D.D., Simpson, J., Cochran, D.L., Boyan, B.D., Effect of titanium surface roughness on chondrocyte proliferation, matrix production, and differentiation depends on the state of cell maturation (1996) J Biomed Mater Res, 30, pp. 145-155; Wang, J., de Boer, J., de Groot, K., Preparation and characterization of electrodeposited calcium phosphate/chitosan coating on Ti 6Al 4V plates (2004) J Dent Res, 83, pp. 296-301; Xavier, S.P., Carvalho, P.S.P., Beloti, M.M., Rosa, A.L., Response of rat bone marrow cells to commercially pure titanium submitted to different surface treatments (2003) J Dent, 31, pp. 173-180
Keywords: article; Atomic force microscopy; Biocompatibility; biomaterial; cell adhesion; Cell Communication; Cell Line, Tumor; cell motility; cell proliferation; cell spreading; cellular distribution; ceramic prosthesis; ceramics; chemistry; confocal laser microscopy; controlled study; Durapatite; Excimer laser; Excimer lasers; human; human cell; Humans; hydroxyapatite; laser; Lasers; material coating; Microchemistry; Microscopy, Atomic Force; Microscopy, Confocal; Microscopy, Electron, Scanning; Microtexture; monolayer culture; osteoblast; Osteoblasts; reproducibility; Scanning electron microscopy; Surface microtopography; Surface modification; Surface Properties; surface property; Surface topography; Surface treatment; Tissue engineering

Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period - Gonçalves, H.; Bernardes, J.; Paula Rocha, A.; Ayres-de-Campos, D. (Early Human DevelopmentEarly Hum. Dev., 2007)
Background: Fetal behavioral states are important indicators of fetal physiology and pathology associated to typical fetal heart rate (FHR) patterns. Aim: To provide linear and nonlinear analysis of FHR patterns associated with fetal behavioral states regarding a better understanding of these states and patterns. Study design and subjects: Fifty FHR tracings from normal term pregnancies with a median duration of 40.3 min were acquired with the SisPorto® 2.01 system for computerized analysis of cardiotocograms. Each tracing was divided into consecutive 10-minute segments and each segment was classified by two experts as pattern A, B, C or D. Outcome measures: Linear and nonlinear indices were computed in each segment, namely mean FHR, long-term irregularity index (LTI), very low (VLF), low (LF) and high (HF) frequency spectral indices, approximate entropy (ApEn) and sample entropy (SampEn). Kappa statistic (κ) and proportions of agreement (Pa) were used for assessment of inter-observer agreement. Bootstrap percentile confidence intervals and nonparametric statistical tests were calculated for statistical inference. Results: Overall agreement between experts in pattern classification was good to excellent with values for κ and Pa of 0.74 (95% CI: 0.64-0.94) and 0.94 (95% CI: 0.92-0.96), respectively. Most linear domain indices increased significantly with rising fetal activity whereas the opposite occurred with nonlinear indices, except for SampEn(2, 0.1). LF/(MF + HF) ratio also significantly increased with fetal activity, denoting an increased sympatho-vagal balance. Conclusions: Results support the hypothesis that entropy and linear variability indices measure different FHR features. FHR patterns associated with active sleep (B) and active wakefulness (D) evidenced more signs of autonomous nervous system activity, with sympatho-vagal imbalance, and less signs related to complexity or irregularity control systems than patterns associated with calm sleep (A) and calm wakefulness (C). © 2006 Elsevier Ireland Ltd. All rights reserved.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: EHDEDdoi: 10.1016/j.earlhumdev.2006.12.006PubMed ID: 17261357Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Universidade do Porto, Faculdade de Ciências, Departamento de Matemática Aplicada, Porto, Portugal; email: hernani.goncalves@fc.up.ptReferences: Nijhuis, J.G., Prechtl, H.F., Martin, C.B.J., Bots, R.S., Are there behavioural states in the human fetus? (1982) Early Hum Dev, 6, pp. 177-195;Nijhuis, I., ten Hof, J., Development of fetal heart rate and behavior: indirect measures to assess the fetal nervous system (1999) Eur J Obstet Gynaecol Reprod Biol, 87, pp. 1-2; Vindla, S., James, D., Fetal behaviour as a test of fetal wellbeing (1995) Br J Obstet Gynaecol, 102, pp. 597-600; Swartjes, J.M., van Geijn, H.P., Mantel, R., van Woerden, E.E., Schoemaker, H.C., Coincidence of behavioural state parameters in the human fetus at three gestational ages (1990) Early Hum Dev, 23, pp. 75-83; Ayres-de-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto® multicentre validation study (2005) Eur J Obstet Gynaecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Bernardes, J., Garrido, A., de Sá, J.M., Pereira-Leite, L., SisPorto 2.0: a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Rooth, G., Huch, A., Huch, R., FIGO news. Guidelines for the use of fetal monitoring (1987) Int J Gynaecol Obstet, 25, p. 159; Bernardes, J., Moura, C., de Sá, J.P.M., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: the effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50 (3), pp. 365-373; Pincus, S., Viscarello, R., Approximate Entropy: a regularity measure for fetal heart rate analysis (1992) Obstet Gynaecol, 79 (2), pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Pincus, S., Approximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Grant, J.M., The fetal heart rate trace is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press; van Woerden, E.E., Geijn, H.P., Caron, F.J., Swartjes, J.M., Mantel, R., Arts, N.F., Automated assignment of behavioural states in the human near term fetus (1989) Early Hum Dev, 19, pp. 137-146; Ten Hof, J., Nijhuis, I.J., Mulder, E.J., Nijhuis, J.G., Narayan, H., Taylor, D.J., Longitudinal study of fetal body movements: nomograms, intrafetal consistency, and relationship with episodes of heart rate patterns A and B (2002) Pediatr Res, 52 (4), pp. 568-575; Bernardes, J., Costa-Pereira, A., de Campos, D.A., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynaecol Obstet, 57 (1), pp. 33-37; Bernardes, J., Costa-Pereira, A., van Geijn, H.P., Pereira-Leite, L., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Mantel, R., van Geijn, H.P., Ververs, I.A., Copray, F.J., Automated analysis of near-term antepartum fetal heart rate in relation to fetal behavioral states: the Sonicaid System 8000 (1992) Am J Obstet Gynaecol, 167 (6), pp. 1912-1914; Court, D.J., Parer, J.T., Experimental studies of fetal asphyxia and fetal heart rate interpretation (1984) Research in perinatal medicine, pp. 113-169. , Nathanielsz P.W., and Parer J.T. (Eds), Perinatology Press, New York; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Bailliere's Clin Obstet Gynaecol, 8 (3), pp. 643-661; van Woerden, E.E., Geijn, H.P., Caron, F.J., Mantel, R., Spectral analysis of fetal heart rhythm in relation to fetal regular mouthing (1990) Int J Biomed Comput, 25 (4), pp. 253-260; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grossesse et de l'accouchement (2004) Encycl Méd-Chir, 148 (5-49 -D-23), pp. 1-10; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Murotsuki, N.Y.J., Uehara, S., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynaecol, 182, pp. 1227-1232; Dawes, G.S., Moulden, M., Sheil, O., Redman, C.W.G., Approximate entropy, a statistic of regularity, applied to fetal heart rate data before and during labour (1992) Obstet Gynaecol, 80 (5), pp. 763-768; Magenes, G., Signorini, M.G., Arduini, D., Cerutti, S., Fetal heart rate variability due to vibroacoustic stimulation: linear and nonlinear contribution (2004) Methods Inf Med, 43 (1), pp. 47-51; Felgueiras, C., de Sá, J.P.M., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed Eng, 36 (2), pp. 197-201; Vieira, P., Marques-de-Sá, J.P., Bernardes, J., Fractal analysis of foetal heart rate (2004) Proceedings of biosignal 2004, pp. 53-55. , Jan J., Kozumplík J., and Provazník I. (Eds), Vutium Press, Brno University of Technology; di Renzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Fractal analysis: a new method for evaluating fetal heart rate variability (1996) J Perinat Med, 24 (3), pp. 261-269
Keywords: adult; article; behavior change; Cardiotocography; Computerized analysis; controlled study; entropy; Female; Fetal behavioral states; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Interpretation, Computer-Assisted; Linear Models; Nonlinear Dynamics; Pregnancy; SisPorto; Spectral analysis; vagus nerve stimulation

Mesenchymal stem cell proliferation and morphological analysis on interconnected macroporous structures - Teixeira, S.; Fernandes, H.M.; De Boer, J.; Ferraz, M.P.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2007)
Calcium phosphate ceramics are widely used as bone substitutes since they are biocompatible and bioactive. Given that their chemical composition is close to natural bone, calcium phosphate ceramics are promising bone substitute materials in orthopaedics, maxillofacial surgery and dentistry. Hydroxyapatite (HA) and tricalcium phosphate (TCP) are the most commonly used calcium phosphates, because their calcium/phosphorus (Ca/P) ratios are close to that of natural bone and they are relatively stable in physiological environment. Furthermore, other critical parameters must be accomplished when designing a biomaterial for bone regeneration, namely: pore size, shape and interconnectivity [1]. Porosity is one of the most important factors since it influences the adhesion, migration nutrient supply and ultimately, proliferation of mesenchymal stem cells. In this study, HA scaffolds with controlled porosity were obtained and their capacity to support human and rat mesenchymal stem cells attachment and proliferation was evaluated.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Teixeira, S.; INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre,823, 4150-180, Porto, Portugal; email: smsilva@ineb.up.ptReferences: Mastrogiacomo, M., (2006) Biomaterials, 27, p. 3230;Queiroz, A.C., Teixeira, S., Monteiro, F.J., Santos, J.D., (2004) Materials, pp. 455,358. , Science Forum; Queiroz, A.C., Teixeira, S., Monteiro, F.J., Santos, J.D., (2004) Key Engineering Materials, pp. 254,997; Moroni, L., (2006) Biomaterials, 27, p. 4911
Keywords: Biomaterials; Calcium Compounds; cell adhesion; cytology; hydroxyapatite; Macroporous ceramics; Mesenchymal Stem Cells; orthopedics; Phase composition; Physiological models; porosity; Tricalcium phosphate (TCP)

Microspheres based on hydroxyapatite nanoparticles aggregates for bone regeneration - Pataquiva Mateus, A.Y.; Ferraz, M.P.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2007)
This study concerns the preparation and characterisation of microspheres associating alginate and two different types of hydroxyapatite (HA), which are intended to be used as drug delivery systems and bone regeneration matrices. Hydroxyapatite nanoparticles (HA-1 and HA-2) were prepared using a chemical precipitation synthesis based on H3PO4, Ca(OH)2 and a surfactant, SDS (sodium dodecylsulphate), as starting reagents. These two powders of nanoHA and alginate were used to prepare two different types of microspheres. Both powders and microspheres were characterised using FTIR, TEM, SEM, mercury porosimetry analysis and X-ray diffraction Results show that pure hydroxyapatite (HA) and mixtures of HA/β-TCP in the nanometre range were obtained from both HA syntheses. Microspheres with different characteristics were obtained from these two types of hydroxyapatite.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Pataquiva Mateus, A.Y.; INEB - Institute de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: yovana@ibmc.up.ptReferences: Liou, S., Chen, S., Liu, D., (2003) Biomaterials, 24, p. 3981;Gauthier, O., Bouler, J., Weiss, P., Bosco, J., Daculsi, G., Aguado, E., (1999) Journal of Biomedical Materials Research, 47, p. 28; Grimaldi, G., Weiss, P., Millot, F., Daculsi, G., (1998) Journal of Biomedical Materials Research, 39, p. 660; Termenoff, J., Mikos, A., (2000) Biomaterials, 21, p. 2405; Best, S., Bonfield, W., Doyle, C., (1989) Bioceramics, p. 68. , Oonishi H, Aoki H, Sawai K, editors, Tokyo: Ishiyaku Euro-America; Pataquiva-Mateus, A.Y., Ferraz, M.P., Monteiro, F.J., Journal of Biomedical Materials Research, , Submitted paper
Keywords: Alginate; Bone; Bone Regeneration; Chemical precipitation; Controlled drug delivery; Fourier transform infrared spectroscopy; hydroxyapatite; Microspheres; Microstructure; nanoparticles; Nanostructured materials; Scanning electron microscopy; Surface active agents; transmission electron microscopy

Nanohydroxyapatite microspheres as delivery system for antibiotics: Release kinetics, antimicrobial activity, and interaction with osteoblasts - Ferraz, M.P.; Mateus, A.Y.; Sousa, J.C.; Monteiro, F.J. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2007)
Severe periodontitis treatment, where massive alveolar bone loss occurs, involves bone defect filling and intensive systemic log-term antibiotics administration. This study aims at developing novel injectable drug delivery systems (nanohydroxyapatite microspheres) with the drug releasing capability for periodontitis treatment and simultaneously initiating the osteointegration process. Materials were characterized by XRD, SEM, inverted stand optical microscope analysis, and mercury porosimetry method. Amoxicillin, amoxicillin + clavulanic acid, and erythromycin were the antibiotics used. Release properties during 28 days from the hydroxyapatite (HA) granules, and two types of nanoHA microspheres were investigated. Biocompatibility was assessed by cytotoxicity assays. HA granules were inadequate, releasing all antibiotic during the first hours. The concentration of antibiotics released in the first days from HA-2 was higher than from HA-1 microspheres, because of the increased porosity and surface area. The release profiles (fast initial release followed by long-term sustained release) of effective doses of antibiotics make these systems good alternatives for antibiotics delivery. Osteoblasts proliferated well on both types of microspheres, being cell growth enhanced in the presence of antibiotics. Erythromycin presented the most beneficial effect. Combining the sustained antibiotic release with the osteoconduction, resorbability, and potential use as injectable bone filling material of porous HA microspheres, these systems provided a forth fold beneficial effect. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31151PubMed ID: 17252559Language of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: mpferraz@ufp.ptChemicals/CAS: amoxicillin, 26787-78-0, 34642-77-8, 61336-70-7; amoxicillin plus clavulanic acid, 74469-00-4, 79198-29-1; clindamycin, 18323-44-9; erythromycin, 114-07-8, 70536-18-4; hydroxyapatite, 1306-06-5, 51198-94-8; metronidazole, 39322-38-8, 443-48-1; minocycline, 10118-90-8, 11006-27-2, 13614-98-7; tetracycline, 23843-90-5, 60-54-8, 64-75-5; Anti-Bacterial Agents; Durapatite, 1306-06-5References: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., Clinical-evaluation of porous and nonporous hydroxyapatite in the treatment of human periodontal bony defects (1987) J Periodontol, 58, pp. 521-528;Kinane, D.F., Lindhe, J., Pathogenesis of periodontitis (2002) Clinical Periodontology and Implant Dentistry, pp. 189-225. , Lindhe J, Karring T, Lang NP, editors, Copenhagen: Munksgaard;; Slots, J., Armitage, G.C., Cochran, D., Cohen, R.E., Greenstein, G., Mariotti, A., Rethman, M.P., and others, Systemic antibiotics in periodontics (1996) J Periodontol, 67, pp. 831-838; Mombelli, A., Antibiotics in periodontal therapy (2002) Clinical Periodontology and Implant Dentistry, , Lindhe J, Karring T, Lang NP, editors, Copenhagen: Munksgaard;; Etienne, D., Locally delivered antimicrobials for the treatment of chronic periodontitis (2003) Oral Dis, 9, pp. 45-50; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Porous HA scaffolds for drug releasing (2005) Bioceramics, 17, pp. 407-410; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Porous hydroxyapatite and glass reinforced hydroxyapatite for controlled release of sodium ampicillin (2004) Bioceramics, 16, pp. 997-1000; Hannes, P.J., Purvis, J.P., Local anti-infective therapy: Pharmacological agents. A systemic review (2003) Ann Periodontol, 8, pp. 79-98; Soskolne, W.A., Heasman, P.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., Sustained local delivery of chlorhexidine in the treatment of periodontitis: A multi-center study (1997) J Periodontol, 68, pp. 32-38; Greenstein, G., Polson, A., The role of local drug delivery in the management of periodontal diseases: A comprehensive review (1998) J Periodontol, 69, pp. 507-520; Killoy, W.J., Chemical treatment of periodontitis: Local delivery of antimicrobials (1998) Int Dent J, 48, pp. 305-315; Schwach-Abdellaoui, K., Vivien-Castioni, N., Gurny, R., Local delivery of antimicrobial agents for the treatment of periodontal diseases (2000) Eur J Pharm Biopharm, 50, pp. 83-99; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Development of a system to adsorb drugs onto calcium phosphate materials (2005) J Mater Sci-Mater Med, 16, pp. 641-646; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Adsorption isotherm of sodium ampicillin onto dense and porous hydroxyapatite (2005) Bioceramics, 17, pp. 387-390; Queiroz, A.C., Santos, J.D., Monteiro, F.J., da Silva, MHP dissolution studies of hydroxyapatite and glass-reinforced hydroxyapatite ceramics (2003) Mater Char, 50, pp. 197-202; Rauschmann, M.A., Wichelhaus, T.A., Stirnal, V., Dingeldein, E., Zichner, L., Schnettler, R., Alt, V., Nanocrystalline hydroxyapatite and calcium sulphate as biodegradable composite carrier material for local delivery of antibiotics in bone infections (2005) Biomaterials, 26, pp. 2677-2684; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Production of porus hydroxyapatite with potential for controlled drug delivery (2004) Mater Sci Forum, 455-456, pp. 358-360; Daculsi, G., Passuti, N., Effect of the macroporosity for osseous substitution of calcium-phosphate ceramics (1990) Biomaterials, 11, pp. 86-87; Gauthier, O., Bouler, J.M., Weiss, P., Bosco, J., Daculsi, G., Aguado, E., Kinetic study of bone ingrowth and ceramic resorption associated with the implantation of different injectable calcium-phosphate bone substitutes (1999) J Biomed Mater Res, 47, pp. 28-35; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) J Biomed Mater Res, 51, pp. 475-483; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Siegel, R.W., Bizios, R., Enhanced surface and mechanical properties of nanophase ceramics to achieve orthopaedic/dental implant efficacy (2000) Bioceramics, 13, pp. 321-324; Liou, S.C., Chen, S.Y., Liu, D.M., Synthesis and characterization of needlelike apatitic nanocomposite with controlled aspect ratios (2003) Biomaterials, 24, pp. 3981-3988; Ferraz, M.P., Monteiro, F.J., Manuel, C.D., Hydroxyapatite nanoparticles: A review of preparation methodologies (2004) J Appl Biomater Biomech, 2, pp. 74-80; Barrias CC, Ribeiro CC, Martins MCL, Barbosa MA, Rodrigues D, Miranda MCS. Calcium phosphate microspheres for localised delivery of a therapeutic enzyme. Bioceramics 2006;18 (Parts 1/2):903-906Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373; Socransky, S.S., Haffajee, A.D., Microbiology of periodontal disease (2002) Clinical Periodontology and Implant Dentistry, , Lindhe J, editor, Copenhagen: Munksgaard;; Slots, J., Selection of antimicrobial agents in periodontal therapy (2002) J Periodontal Res, 37, pp. 389-398; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Preparation and characterisation of calcium-phosphate porous microspheres with a uniform size for biomedical applications (2006) J Mater Sci-Mater Med, 17, pp. 455-463; Barrias, C.C., Ribeiro, C.C., Lamghari, M., Sá, C., Barbosa, M.A., Proliferation, activity and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) J Biomed Mater Res A, 72, pp. 57-66; Mateus, A.Y.P., Ferraz, M.P., Monteiro, F.J., Comparative study of injectable material synthesised from alginate and two types of hydroxyapatite Submitted for publicationFerraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P2O5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro bioactivity evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Nakamura, T., Kitsogi, T., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J Biomed Mater Res, 24, pp. 471-488; Gautier, H., Daculsi, G., Merle, C., Association of vancomycin and calcium phosphate by dynamic compaction: In vitro characterization and microbiological activity (2001) Biomaterials, 22, pp. 2481-2487; Kimakhe, S., Bohic, S., Larrose, C., Reynaud, A., Pilet, P., Giumelli, B., Heymann, D., Daculsi, G., Biological activities of sustained polymyxin B release from calcium phosphate biomaterial prepared by dynamic compaction: An in vitro study (1999) J Biomed Mater Res, 47, pp. 18-27; Korkusuz, F., Uchida, A., Shinto, Y., Araki, N., Inoue, K., Ono, K., Experimental implant-related osteomyelitis treated by antibiotic-calcium hydroxyapatite ceramic composites (1993) J Bone Joint Surg-Br, 75, pp. 111-114; Otsuka, M., Matsuda, Y., Kokubo, T., Yoshihara, S., Nakamura, T., Yamamuro, T., A novel skeletal drug-delivery system using self-setting bioactive glass bone-cement. II. Drug-release from a novel self-setting bioactive glass bone-cement containing cephalexin and its physicochemical properties (1995) J Biomed Mater Res, 29, pp. 33-38; Shinto, Y., Uchida, A., Korkusuz, F., Araki, N., Ono, K., Calcium hydroxyapatite ceramic used as a delivery system for antibiotics (1992) J Bone Joint Surg Br, 74, pp. 600-604; Yamamura, K., Iwata, H., Yotsuyanagi, T., Synthesis of antibiotic-loaded hydroxyapatite beads and invitro drug release testing (1992) J Biomed Mater Res, 26, pp. 1053-1064; Clover, J., Gowen, M., Are Mg-63 and Hos Te85 human osteosarcoma cell-lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591
Keywords: alveolar bone; amoxicillin; amoxicillin plus clavulanic acid; Anti-Bacterial Agents; Antibacterial; antibiotic agent; antibiotic resistance; Antibiotics administration; antimicrobial activity; article; Bacteria; Cell Communication; Cell Death; cell growth; cell kinetics; Cell Line; cell proliferation; clindamycin; concentration response; controlled study; Cytotoxicity; Drug delivery; drug delivery system; Drug Delivery Systems; Drug release; Durapatite; erythromycin; Escherichia coli; human; human cell; Humans; hydroxyapatite; Kinetics; materials testing; metronidazole; Microbial Sensitivity Tests; microsphere; Microspheres; minocycline; Nanohydroxyapatite; nanoparticle; nanoparticles; nonhuman; Optical microscope analysis; osteoblast; Osteoblasts; osteolysis; periodontitis; porosity; Staphylococcus aureus; surface property; sustained drug release; Tetracycline; unclassified drug; X ray diffraction

A novel dry active electrode for EEG recording - Fonseca, C.; Silva Cunha, J.P.; Martins, R.E.; Ferreira, V.M.; Marques De Sá, J.P.; Barbosa, M.A.; Martins Da Silva, A. (IEEE Transactions on Biomedical EngineeringIEEE Trans. Biomed. Eng., 2007)
The design and testing of a "dry" active electrode for electroencephalographic recording is described. A comparative study between the EEG signals recorded in human volunteers simultaneously with the classical Ag-AgCl and "dry" active electrodes was carried out and the reported preliminary results are consistent with a better performance of these devices over the conventional Ag-AgCl electrodes. © 2007 IEEE.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusArt. No.: 23CODEN: IEBEAdoi: 10.1109/TBME.2006.884649PubMed ID: 17260869Language of Original Document: EnglishCorrespondence Address: Fonseca, C.; INEB Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Universidade Do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cfonseca@ibmc.up.ptChemicals/CAS: Biocompatible Materials; Titanium, 7440-32-6; titanium dioxide, 13463-67-7References: Portnoy, W., David, R., Akers, L., Insulated ECG electrodes (1974) Biomedical Electrode Technology, , H. A. Miller and D. C. Harrison, Eds. New York: Academic;Nishimura, S., Tomita, Y., Horiuchi, T., Clinical application of an active electrode using an operational amplifier (1992) IEEE Trans. Biomed. Eng, 39 (10), pp. 1090-1099. , Oct; Taheri, A., Knight, R., Smith, R., A dry electrode for EEG recording (1994) Electroencephalogr. Clin. Neurophysiol, 90, pp. 376-383; Searle, A., Kirkup, L., A direct comparison of wet, dry and insulating bioelectric recording electrodes (2000) Physiol. Meas, 22, pp. 71-83; Fonseca, C., Vaz, F., Barbosa, M.A., Electrochemical behaviour of titanium coated stainless steel by R.F. sputtering in synthetic sweat solutions for electrode applications (2004) Corrosion Sci, 46 (12), pp. 3005-3018; Matsuo, T., IInuma, K., Esashi, M., Barium titanate ceramics capacitive type EEG elecrode (1973) IEEE Trans. Biomed. Eng, BME-20, pp. 299-300; Perez, J., Vilarinho, P., Kholkin, A., High-quality Pbzr0.52Ti0. 48O3 films prepared by modified sol-gel route at low temperature (2004) Thin Solid Films, 449 (1-2), pp. 20-24; Rosell, J., Colominas, J., Riu, P., Pallas-Areny, R., Webster, J., Skin impedance from 1 Hz to 1 MHz (1988) IEEE Trans. Biomed. Eng, 35 (8), pp. 649-651. , Aug; Ferree, T., Luu, P., Russell, G., Tucker, D., Scalp electrode impedance, infection risk and EEG data quality (2001) Clin. Neurophysiol, 112 (3), pp. 536-544
Keywords: article; Biocompatible Materials; Bioelectric phenomena; Bioelectric signal recording; bioenergy; biomedical electrodes; Biomedical engineering; Data recording; Dry electrodes; Electric Impedance; Electrochemical electrodes; electrode; Electrodes; electroencephalogram; Electroencephalographic recording; electroencephalography; Equipment Design; Equipment Failure Analysis; Feasibility Studies; Pilot Projects; signal transduction; Silver compounds; Titanium

Opening wedge high tibial osteotomy using 3D biomodelling Bonelike® macroporous structures: Case report - Gutierres, M.; Dias, A.G.; Lopes, M.A.; Hussain, N.S.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2007)
Two synthetic calcium phosphates in porous wedge shape, Bonelike® and a commercial HA/β-TCP biphasic material, were used as an alternative to bone autografts and allografts in the treatment of medial compartment osteoarthritis of varus knees. The structure of Bonelike® has a 3D architecture that is computer controlled, and a composition that mimics the mineral composition of natural bone. The HA/β-TCP biphasic material used as a control material in this study was prepared using conventional foaming based methods. No signs of inflammatory reactions were observed post-operatively for both materials. After 4 months signs of fusion at the osteotomy site and good integration of the implanted wedges were observed, showing good mechanical resistance. Concerning the final correction attained, the left knee revealed a satisfactory valgus of 10°, but the right one only had a final value of 6°. The clinical evaluation using International Knee Score (IKS) showed good outcome in all parameters with complete range of motion in both knees and climbing stairs without crutches with only slight pain. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3171-xPubMed ID: 17569003Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Instituto de Engenharia Biomédica (INEB), Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Bone Substitutes; Calcium Phosphates; Ceratite, 124097-42-3; HydroxyapatitesTradenames: BonelikeReferences: Gaasbeek, R.D.A., Welsing, R.T.C., Verdonschot, N., Rijnberg, W.J., Van Loon, C.J.M., Van Kampen, A., (2005) Knee Surg. Sports Traumatol. Arthrosc., 13, p. 689. , 8;Scott, W.N., Clarke, H.D., (2004) Orthopedics, 27, p. 975. , 9; Virolainen, P., Aro, H.T., (2004) Arch. Orthop. Trauma Surg., 124, p. 258. , 4; Wright, J.M., Crockett, H.C., Slawski, D.P., Madsen, M.W., Windsor, R.E., (2005) J. Am. Acad. Orthop. Surg., 13, p. 279. , 4; Fujisawa, Y., Masura, K., Shiomi, S., (1979) Clin. Orthop. North Am., 10, p. 585; Odenbridge, S., Egund, N., Lindstrand, A., Lohmander, L.S., Willen, H., (1992) Clin Orthop., 277, p. 210; Koshino, T., Wada, S., Ara, Y., Saito, T., (2003) Knee, 10, p. 229; Hernigou, P., (2002) Knee, 9, p. 15. , 1; Hoell, S., Suttmoeller, J., Stoll, V., Fuchs, S., Gosheger, G., (2005) Arch. Orthop. Trauma Surg., 125, p. 638. , 9; Betz, R.R., (2002) Orthopedics, 25, p. 561. , 5; Legeros, R.Z., (2002) Clin. Orthop. Relat. Res., 395, p. 81; Steffen, T., Stoll, T., Arvinte, T., Schenk, R.K., (2001) Eur. Spine J., 10, p. 132; Chu, T.M.G., Orton, D.G., Hollister, S.J., Feinberg, S.E., Halloran, J.W., (2002) Biomaterials, 23, p. 1283. , 5; Hutmacher, D.W., Sittinger, M., Risbud, M.V., (2004) Trends Biotechnol., 22, p. 354. , 7; Jones, J.R., Ehrenfried, L.M., Hench, L.L., (2006) Biomaterials, 27, p. 964. , 7; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19, p. 133. , 1-3; LU, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci. Mater. Med., 10, p. 111. , 2; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26, p. 5609. , 28; Moroni, L., De Wijn, J.R., Van Blitterswijk, C.A., (2006) Biomaterials, 27, p. 974. , 7; Duarte, F., Santos, J.D., Afonso, A., (2004) Adv. Mater. Forum, 455-456, p. 370; Lobato, J.V., Hussain, N.S., Botelho, C.M., Mauricio, A.C., Lobato, J.M., Lopes, M.A., Afonso, A., Santos, J.D., (2006) Thin Solid Films, 515, p. 279. , 1; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., (2005) Bioceramics, 17, p. 1041; Lobato, J.V., Hussain, N.S., Botelho, C.M., Rodrigues, J.M., Luís, A.L., Maurício, A.C., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 877; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Leong, K.F., Cheah, C.M., Chua, C.K., (2003) Biomaterials, 24, p. 2363. , 13; Hutmacher, D.W., (2001) J. Biomater. Sci. Polym. Ed., 12, p. 107. , 1; Santos, J., Hastings, G., Knowles, J., Sintered hydroxyapatite compositions and method for the preparation thereof (1999), Worldwide Application (PCT), Patent No. 1 189 851Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244. , 2; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905. , 18; Schwartz, C., Liss, P., Jacquemaire, B., Lecestre, P., Frayssinet, P., (1999) J. Mater. Sci. Mater. Med., 10, p. 821. , 12; Van Hemert, W.L.W., Willems, K., Anderson, P.G., Van Heerwaarden, R.J., Wymenga, A.B., (2004) Knee, 11, p. 451. , 6; Gaasbeek, R.D.A., Toonen, H.G., Van Heerwaarden, R.J., Buma, P., (2005) Biomaterials, 26, p. 6713. , 33; Hernigou, P., Ma, W., (2001) Knee, 8, p. 103. , 2; Koshino, T., Murase, T., Saito, T., (2003) J. Bone Joint Surg. Am., 85, p. 78. , 1; Koshino, T., Murase, T., Takagi, T., Saito, T., (2001) Biomaterials, 22, p. 1579. , 12; Zhim, F., Laflamme, G.Y., Viens, H., Saidane, K., Yahia, L., (2005) Clin. Biomech., 20, p. 871. , 8; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085. , 21; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 48, p. 734. , 5
Keywords: adult; article; Biological organs; Biomodeling; Bone; bone allograft; Bone graft; bone mineral; Bone Substitutes; calcium phosphate; Calcium phosphates; case report; climbing; clinical evaluation; Computer simulation; Grafts; human; Humans; hydroxyapatite; Hydroxyapatites; Imaging, Three-Dimensional; knee; knee pain; Macroporous structures; male; Mechanical properties; Middle Aged; Osteoarthritis; Osteoarthritis, Knee; Osteoblasts; osteotomy; pain assessment; porosity; Porous wedge shapes; priority journal; Prostheses and Implants; range of motion; structure analysis; tibia; tibia osteotomy; Tibial osteotomy; Valgus; valgus knee

Physicochemical degradation studies of calcium phosphate glass ceramic in the CaO-P 2O 5-MgO-TiO 2 system - Dias, A.G.; Gibson, I.R.; Santos, J.D.; Lopes, M.A. (Acta BiomaterialiaActa Biomater., 2007)
The aim of this work was to evaluate the in vitro degradation behaviour of a 45CaO-37P 2O 5-5MgO-13TiO 2 (mol.%) glass ceramic, under two different simulated physiological conditions: normal physiological pH 7.4, and pH 3.0, which was designed to simulate the acidic conditions produced by osteoclast cells. The in vitro testing was carried out at 37 °C for up to 42 days for the pH 7.4 solution and for up to 1 day for the pH 3.0 solution. The incorporation of TiO 2 into the glass structure leads to the precipitation of specific crystalline phases in the glass matrix, namely α- and β-Ca 2P 2O 7, TiP 2O 7 and CaTi 4(PO 4) 6. The degradation testing at pH 3.0 showed a higher weight loss compared with degradation testing at pH 7.4; the weight loss under the acidic condition after 1 day (24 h) was about 10 times higher than the weight loss after 42 days of immersion at pH 7.4. The ionic release profile of Ca 2+, PO 4 3 -, Mg 2+ and Ti 4+ showed a continuous increase in concentration over all immersion times for both testing solutions. After 1 day of immersion at pH 3.0, the concentration levels of Mg 2+, Ca 2+, PO 4 3 - were about six times higher than the levels achieved after 42 days of immersion at pH 7.4. The glass ceramic showed similar degradation to hydroxyapatite, and therefore has potential to be used in certain clinical applications where relatively slow resorption of the implant and replacement by bone is required, e.g. cranioplasty. © 2006 Acta Materialia Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2006.09.009PubMed ID: 17150421Language of Original Document: EnglishCorrespondence Address: Lopes, M.A.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: malopes@fe.up.ptChemicals/CAS: calcium ion, 14127-61-8; hydroxyapatite, 1306-06-5, 51198-94-8; phosphate, 14066-19-4, 14265-44-2; titanium, 7440-32-6; Biocompatible Materials; Calcium Compounds; calcium phosphate, 10103-46-5; Calcium Phosphates; Ceramics; Glass ceramics, 85422-94-2; lime, 1305-78-8; Magnesium Oxide, 1309-48-4; Oxides; Phosphorus Compounds; phosphorus pentoxide, 1314-56-3; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: (2003) Bone graft substitutes, , Laurencin C.T. (Ed), ASTM International;(1993) Introduction to bioceramics, , Hench L.L., and Wilson J. (Eds), World Scientific, Singapore; Ratner, B.D., Bryant, S.J., Biomaterials: where we have been and where we are going (2004) Ann Rev Biomed Eng, 6, p. 41; Fuchs, J.R., Nasseri, B.A., Vacanti, J.P., Tissue engineering: a 21st century solution to surgical reconstruction (2001) Ann Thorac Surg, 72, p. 577; Nasseri, B.A., Ogawa, K., Vacanti, J.P., Tissue engineering: an evolving 21st-century science to provide biologic replacement for reconstruction and transplantation (2001) Surgery, 130, p. 781; Stock, U.A., Vacanti, J.P., Tissue engineering: current state and prospects (2001) Ann Rev Med, 52, p. 443; Burnie, J., Gilchrist, T., Controlled release glass (CRG) - a new biomaterials (1983) Ceramics in Surgery, p. 169. , Vicenzi P. (Ed), Elsevier, Amsterdam; Burnie, J., Gilchrist, T., Duff, S.R.I., Drake, C.F., Harding, N.G.L., Malcolm, A.J., Controlled release glasses (CRG) for biomedical uses (1981) Biomaterials, 2, p. 244; (2004) Biomaterials Science: An Introduction to Materials in Medicine, , Ratner B.D., Hoffmam A.S., Schoen F.J., and Lemons F.J. (Eds), Elsevier, Amsterdam; Vogel, J., Wange, P., Hartmann, P., Phosphate glasses and glass-ceramics for medical applications (1997) Glastech Ber-Glass, 70, p. 220; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angew Chem Int Edit, 41, p. 3130; Grambow, B., Geochemical approach to glass dissolution (1992) Corrosion of Glass, Ceramics and Ceramic Superconductors, , Clark D.E., and Zoitos B.K. (Eds), Noyes, Park Ridge, NJ; Legeros, R.Z., Biodegradation and bioresorption of calcium phosphate ceramics (1993) Clin Mater, 14, p. 65; Lettuec, J.C., Clément, D., Lesprit, E., Faber, J., The use of calcium phosphates, their biological properties (2000) Eur J Orthopaedic Surg Traumatol, 10, p. 223; McCracken, W.J., Corrosion of glass-ceramics (1992) Corrosion of Glass, Ceramics and Ceramic Superconductors, , Clark D.E., and Zoitos B.K. (Eds), Noyes, Park Ridge, NJ; Dias, A.G., Costa, M.A., Lopes, M.A., Santos, J.D., Fernandes, M.H., Biological activity of two glass ceramics in the meta- and pyrophosphate region: a comparative study (2004) Key Eng Mater, 254-256, p. 825; Dias, A.G., Lopes, M.A., Afonso, A.A., Tsuru, K., Hayakawa, S., Takashima, S., In vivo performance of biodegradable calcium phosphate glass ceramics using the rabbit model: histological and SEM observation (2006) J Biomater Appl, 20, p. 253; Dias, A.G., Lopes, M.A., Cabral, A.T.T., Santos, J.D., Fernandes, M.H., In vitro studies of calcium phosphate glass ceramics with different solubility with the use of human bone marrow cells (2005) J Biomed Mater Res A, 74 A, p. 347; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., In situ thermal and structural characterization of bioactive calcium phosphate glass ceramics containing TiO 2 and MgO oxides: high temperature XRD studies (2005) J Non-Cryst Solids, 351, p. 810; Baron, R., Neff, L., Louvard, D., Courtoy, P.J., Cell-mediated extracellular acidification and bone-resorption - evidence for a low ph in resorbing lacunae and localization of a 100-kD lysosomal membrane-protein at the osteoclast ruffled border (1985) J Cell Biol, 101, p. 2210; Teitelbaum, S.L., Bone resorption by osteoclasts (2000) Science, 289, p. 1504; Dias, A.G., Tsuru, K., Hayakawa, T., Lopes, M.A., Santos, J.D., Osaka, A., Crystallisation studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications (2004) Glass Tech, 45, p. 78; Nyquist, R.A., (1997) Handbook of infrared and raman spectra of inorganic compounds and organics salts, , Academic Press, New York; Tadic, D., Epple, M., A thorough physicochemical characterisation of 14 calcium phosphate-based bone substitution materials in comparison to natural bone (2004) Biomaterials, 25, p. 987; Ploska, U., Berger, G., Solubility of compositions in the system CaTixZr 4 - x(PO 4) 6 with x = 0-4 (1997) Biomaterials, 18, p. 1671; Lin, F.H., Liao, C.J., Chen, K.S., Sun, J.S., Liu, H.C., Degradation behaviour of a new bioceramic: Ca 2P 2O 7 with addition of Na 4P 2O 7 · 10H 2O (1997) Biomaterials, 18, p. 915; Koerten, H.K., van der Meulen, J., Degradation of calcium phosphate ceramics (1999) J Biomed Mater Res, 44, p. 78; Athanasou, N.A., Cellular biology of bone-resorbing cells (1996) J Bone Joint Surg Am, 78, p. 1096; Aoki, H., (1991) Science and medical applications of hydroxyapatite, , Takayama Press, Tokyo; Aoki, H., (1994) Medical applications of hydroxypatite, , Ishiyaku EuroAmerica, Inc., Tokyo; Hennequin, M., Douillard, Y., Effects of citric-acid treatment on the Ca, P and Mg contents of human dental roots (1995) J Clin Periodontol, 22, p. 550; Hennequin, M., Pajot, J., Avignant, D., Effects of different pH values of citric-acid solutions on the calcium and phosphorus contents of human root dentin (1994) J Endod, 20, p. 551; Misra, D.N., Interaction of citric-acid with hydroxyapatite - formation of calcium citrate (1995) J Dent Res, 74, p. 72; Misra, D.N., Interaction of citric acid with hydroxyapatite: surface exchange of ions and precipitation of calcium citrate (1996) J Dent Res, 75, p. 1418; Ribeiro, C.C., Barbosa, M.A., Machado, A., Tudor, A., Davies, M.C., Modifications in the molecular structure of hydroxyapatite induced by titanium ions (1995) J Mater Sci Mater Med, 6, p. 829; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Al 3+ and La 3+ ions in acidic solutions (1990) J Chem Soc Faraday T, 86, p. 4025; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Fe 2+ and Fe 3+ ions (1990) J Chem Soc Faraday T, 86, p. 1071; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue response in the femur of rabbits after implantation of a new calcium titanium phosphate composition (2001) Key Eng Mater, 192-195, p. 383; Kitsugi, T.l.T., Yamamuro, T., Nakamura, T., Oka, M., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorous molar ratios (1995) Biomaterials, 16, p. 1101; Sun, J.-S., Chang, W.H.-S., Chen, L.-T., Huang, Y.-C., Juang, L.-W., Lin, F.-H., The influence on gene-expression profiling of osteoblasts behavior following treatment with the ionic products of sintered β-dicalcium pyrophosphate dissolution (2004) Biomaterials, 25, p. 607; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., Biodegradation study of potassium calcium metaphosphate in the SBF and Tris-buffer solution (2002) Key Eng Mater, 218-220, p. 149
Keywords: acidity; article; Biocompatible Materials; Biomaterials; Bone; Bone and Bones; bone prosthesis; Calcium Compounds; calcium ion; calcium phosphate ceramic; Calcium phosphates; ceramics; Chemical structure; concentration response; controlled study; cranioplasty; Crystallization; Degradation; glass; Hydrogen-Ion Concentration; hydroxyapatite; In vitro biodegradation; in vitro study; Magnesium Oxide; materials testing; Microscopy, Electron, Scanning; Models, Statistical; osteoclast; Oxides; pH; phosphate; Phosphorus Compounds; physical chemistry; priority journal; prosthesis material; simulation; Spectrum Analysis, Raman; structure analysis; temperature; Time Factors; Titanium; weight reduction

Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix - Evangelista, M.B.; Hsiong, S.X.; Fernandes, R.; Sampaio, P.; Kong, H.-J.; Barrias, C.C.; Salema, R.; Barbosa, M.A.; Mooney, D.J.; Granja, P.L. (BiomaterialsBiomaterials, 2007)
There is a need for new therapeutic strategies to treat bone defects caused by trauma, disease or tissue loss. Injectable systems for cell transplantation have the advantage of allowing the use of minimally invasive surgical procedures, and thus for less discomfort to patients. In the present study, it is hypothesized that Arg-Gly-Asp (RGD)-coupled in a binary (low and high molecular weight) injectable alginate composition is able to influence bone cell differentiation in a three-dimensional (3D) structure. Viability, metabolic activity, cytoskeleton organization, ultrastructure and differentiation (alkaline phosphatase (ALP), von Kossa, alizarin red stainings and osteocalcin quantification) of immobilized cells were assessed. Cells within RGD-modified alginate microspheres were able to establish more interactions with the synthetic extracellular matrix as visualized by confocal laser scanning microscope and transmission electron microscopy imaging, and presented a much higher level of differentiation (more intense ALP and mineralization stainings and higher levels of osteocalcin secretion) when compared to cells immobilized within unmodified alginate microspheres. These findings demonstrate that peptides covalently coupled to alginate were efficient in influencing cell behavior within this 3D system, and may provide adequate preparation of osteoblasts for cell transplantation. © 2007 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2007.04.028PubMed ID: 17532040Language of Original Document: EnglishCorrespondence Address: Evangelista, M.B.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: mbe@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; DNA, 9007-49-2; osteocalcin, 136461-80-8; Alginates; alginic acid, 9005-32-7; Alkaline Phosphatase, EC 3.1.3.1; arginyl-glycyl-aspartic acid, 99896-85-2; Glucuronic Acid, 576-37-4; Hexuronic Acids; Oligopeptides; Osteocalcin, 104982-03-8References: de Vos, P., de Haan, B., Wolters, G.H.J., VanSchilfgaarde, R., Factors influencing the adequacy of microencapsulation of rat pancreatic islets (1996) Transplantation, 62 (7), pp. 888-893;Brissova, M., Lacik, I., Powers, A.C., Anilkumar, A.V., Wang, T., Control and measurement of permeability for design of microcapsule cell delivery system (1998) J Biomed Mater Res, 39 (1), pp. 61-70; Strand, B.L., Gaserod, O., Kulseng, B., Espevik, T., Skjak-Braek, G., Alginate-polylysine-alginate microcapsules: effect of size reduction on capsule properties (2002) J Microencapsul, 19 (5), pp. 615-630; Chang, T.M.S., Artificial liver support based on artificial cells with emphasis on encapsulated hepatocytes (1992) Artif Organs, 16 (1), pp. 71-74; Uludag, H., Sefton, M.V., Microencapsulated human hepatoma (HepG2) cells-in-vitro growth and protein release (1993) J Biomed Mater Res, 27 (10), pp. 1213-1224; Canaple, L., Rehor, A., Hunkeler, D., Improving cell encapsulation through size control (2002) J Biomater Sci Polym Ed, 13 (7), pp. 783-796; Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomaterials, 21 (23), pp. 2405-2412; LeBaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: functional applications in orthopedic materials (2000) Tissue Eng, 6 (2), pp. 85-103; Gumbiner, B.M., Cell adhesion: the molecular basis of tissue architecture and morphogenesis (1996) Cell, 84 (3), pp. 345-357; Majmudar, G., Bole, D., Goldstein, S.A., Bonadio, J., Bone cell-culture in a 3-dimensional polymer bead stabilizes the differentiated phenotype and provides evidence that osteoblastic cells synthesize type-III collagen and fibronectin (1991) J Bone Miner Res, 6 (8), pp. 869-881; Payne, R.G., Yaszemski, M.J., Yasko, A.W., Mikos, A.G., Development of an injectable, in situ crosslinkable, degradable polymeric carrier for osteogenic cell populations. Part 1. Encapsulation of marrow stromal osteoblasts in surface crosslinked gelatin microparticles (2002) Biomaterials, 23 (22), pp. 4359-4371; Lee, K.Y., Alsberg, E., Mooney, D.J., Degradable and injectable poly(aldehyde guluronate) hydrogels for bone tissue engineering (2001) J Biomed Mater Res, 56 (2), pp. 228-233; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dental Res, 80 (11), pp. 2025-2029; Burdick, J.A., Anseth, K.S., Photoencapsulation of osteoblasts in injectable RGD-modified PEG hydrogels for bone tissue engineering (2002) Biomaterials, 23 (22), pp. 4315-4323; Smidsrod, O., Skjak-Braek, G., Alginate as immobilization matrix for cells (1990) Trends Biotechnol, 8 (3), pp. 71-78; Boontheekul, T., Kong, H.J., Mooney, D.J., Controlling alginate gel degradation utilizing partial oxidation and bimodal molecular weight distribution (2005) Biomaterials, 26 (15), pp. 2455-2465; Kong, H.J., Alsberg, E., Kaigler, D., Lee, K.Y., Mooney, D.J., Controlling degradation of hydrogels via the size of cross-linked junctions (2004) Adv Mater, 16 (21), pp. 1917-1921; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20 (1), pp. 45-53; Bouhadir, K.H., Lee, K.Y., Alsberg, E., Damm, K.L., Anderson, K.W., Mooney, D.J., Degradation of partially oxidized alginate and its potential application for tissue engineering (2001) Biotechnol Prog, 17 (5), pp. 945-950; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029; Bouhadir, K.H., Hausman, D.S., Mooney, D.J., Synthesis of cross-linked poly(aldehyde guluronate) hydrogels (1999) Polymer, 40 (12), pp. 3575-3584; Labarca, C., Paigen, K., Simple, rapid, and sensitive DNA assay procedure (1980) Anal Biochem, 102 (2), pp. 344-352; Caron, J.M., Kirschner, M.W., Autoregulation of tubulin synthesis (1986) Bioessays, 5 (5), pp. 211-216; Poole, C.A., Brookes, N.H., Clover, G.M., Keratocyte networks visualised in the living cornea using vital dyes (1993) J Cell Sci, 106, pp. 685-691; Li, R.H., Altreuter, D.H., Gentile, F.T., Transport characterization of hydrogel matrices for cell encapsulation (1996) Biotechnol Bioeng, 50 (4), pp. 365-373; Dulieu, C., Poncelet, D., Neufeld, R.J., Encapsulation and immobilization techniques (1999) Cell encapsulation technology and therapeutics, pp. 3-17. , Kühtreiber W.M., Lanza R.P., and Chick W.L. (Eds), Birkhäuser, Boston; Peirone, M., Ross, C.J.D., Hortelano, G., Brash, J.L., Chang, P.L., Encapsulation of various recombinant mammalian cell types in different alginate microcapsules (1998) J Biomed Mater Res, 42 (4), pp. 587-596; Kong, H.J., Kaigler, D., Kim, K., Mooney, D.J., Controlling rigidity and degradation of alginate hydrogels via molecular weight distribution (2004) Biomacromolecules, 5 (5), pp. 1720-1727; Boninsegna, S., Dal Toso, R., Dal Monte, R., Alginate microspheres loaded with animal cells and coated by a siliceous layer (2003) J Sol-Gel Sci Technol, 26 (1-3), pp. 1151-1157; Rokstad, A.M., Donati, I., Borgogna, M., Oberholzer, J., Strand, B.L., Espevik, T., Cell-compatible covalently reinforced beads obtained from a chemoenzymatically engineered alginate (2006) Biomaterials, 27 (27), pp. 4726-4737; Lu, M.Z., Lan, H.L., Wang, F.F., Chang, S.J., Wang, Y.J., Cell encapsulation with alginate and alpha-phenoxycinnamylidene-acetylated poly(allylamine) (2000) Biotechnol Bioeng, 70 (5), pp. 479-483; Stein, G.S., Lian, J.B., Molecular mechanisms mediating proliferation differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocrine Rev, 14 (4), pp. 424-442; Siebers, M.C., ter Brugge, P.J., Walboomers, X.F., Jansen, J.A., Integrins as linker proteins between osteoblasts and bone replacing materials. A critical review (2005) Biomaterials, 26 (2), pp. 137-146; Hynes, R.O., Integrins: bidirectional, allosteric signaling machines (2002) Cell, 110 (6), pp. 673-687; Giancotti, F.G., Ruoslahti, E., Transduction-integrin signaling (1999) Science, 285 (5430), pp. 1028-1032; Payne, R.G., McGonigle, J.S., Yaszemski, M.J., Yasko, A.W., Mikos, A.G., Development of an injectable, in situ crosslinkable, degradable polymeric carrier for osteogenic cell populations. Part 2. Viability of encapsulated marrow stromal osteoblasts cultured on crosslinking poly(propylene fumarate) (2002) Biomaterials, 23 (22), pp. 4373-4380; Franceschi, R.T., Iyer, B.S., Relationship between collagen-synthesis and expression of the osteoblast phenotype in MC3T3-E1 cells (1992) J Bone Miner Res, 7 (2), pp. 235-246; Franceschi, R.T., The developmental control of osteoblast-specific gene expression: role of specific transcription factors and the extracellular matrix environment (1999) Crit Rev Oral Biol Med, 10 (1), pp. 40-57; Gerstenfeld, L.C., Chipman, S.D., Kelly, C.M., Hodgens, K.J., Lee, D.D., Landis, W.J., Collagen expression, ultrastructural assembly, and mineralization in cultures of chicken-embryo osteoblasts (1988) J Cell Biol, 106 (3), pp. 979-989; Dudley, H.R., Spiro, D., Fine structure of bone cells (1961) J Biophys Biochem Cytol, 11 (3), pp. 627-649; Holtrop, M.E., The ultrastructure of bone (1975) Ann Clin Lab Sci, 5 (4), pp. 264-271; Rhodin, J.A.G., (1963) An atlas of ultrastructure, , W. B. Saunders Company, Philadelphia; Trojani, C., Weiss, P., Michiels, J.F., Vinatier, C., Guicheux, J., Daculsi, G., Three-dimensional culture and differentiation of human osteogenic cells in an injectable hydroxypropylmethylcellulose hydrogel (2005) Biomaterials, 26 (27), pp. 5509-5517; Kneser, U., Voogd, A., Ohnolz, J., Buettner, O., Stangenberg, L., Zhang, Y.H., Fibrin gel-immobilized primary osteoblasts in calcium phosphate bone cement: in vivo evaluation with regard to application as injectable biological bone substitute (2005) Cells Tissues Organs, 179 (4), pp. 158-169; Bancroft, J.D., Gamble, M., (2002) Theory and practice of histological techniques. 5th ed, , Elsevier Science, Edinburgh
Keywords: 3T3 Cells; Alginate; Alginates; alginic acid; alkaline phosphatase; animal cell; Animals; arginylglycylaspartic acid; article; Bone; bone cell; Bone Regeneration; calvaria; cell adhesion; cell differentiation; Cell encapsulation; Cell immobilization; cell metabolism; cell proliferation; cell survival; cell ultrastructure; cell viability; confocal laser microscopy; controlled study; cytology; cytoskeleton; DNA; DNA content; ECM (extracellular matrix); enzyme activity; extracellular matrix; Glucuronic Acid; Hexuronic Acids; hydrogel; immobilized cell; metabolism; Mice; Microscopy, Confocal; Microscopy, Electron, Transmission; microsphere; Microspheres; nonhuman; Oligopeptides; osteoblast; Osteoblasts; osteocalcin; Patient treatment; priority journal; rat; RGD peptide; structure analysis; three dimensional imaging; Tissue engineering; transmission electron microscopy; Transplantation (surgical)

31P MAS-NMR studies of CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Tsuru, K.; Hayakawa, S.; Santos, J.D.; Osaka', A. (Key Engineering MaterialsKey Eng Mat, 2006)
This work reports the structure of two glass ceramics prepared in the calcium phosphate system, MK5B and MT13B, using 31P MAS-NMR technique. The results obtained showed that the network of MK5B consisted mainly of Q 1 and Q 2 groups. Besides these two groups, MT13B material also present Q 3 units. The Q n groups detected in both glass ceramics seem to be correlated to the crystalline phases present in their microstructure.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Dias, A.G.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: agdias@fe.up.ptReferences: Jäger, C., Hartmann, P., Witter, R., Braun, M., (2000) J. Non-cryst. Solids, 263, p. 61;Hartmann, P., Vogel, J., Schnabel, B., (1994) J. Non-cryst. Solids, 176, p. 157; Dias, A.G., Lopes, M.A., Gibson, I.R., Santos, J.D., (2003) J. Non-cryst. Solids, 330, p. 81; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., (2005) J. Non-cryst. Solids, 351, p. 810; Brow, R.K., (2000) J. Non-cryst. Solids, 263, p. 1; Hayakawa, S., Tsuru, S., Iida, H., Ohtsuki, C., Osaka, A., (1996) Phys. Chem. Glasses, 37, p. 188; Brown, R.K., Tallant, D.R., Warren, W.L., McIntyre, A., Day, D.E., (1997) Phys. Chem. Glasses, 38, p. 300; Kirkpatrick, R.J., Brown, R.K., (1995) Sol. Stat. Nucl. Mag. Resonance, 5, p. 9
Keywords: Biomaterials; calcium phosphate; Crystalline materials; Crystalline phases; Glass ceramics; Lime; MAS-NMR technique; Microstructure; NMR; Nuclear magnetic resonance spectroscopy

Absorption and emission properties of Ho 3+ doped lead-zinc-borate glasses - Sooraj Hussain, N.; Ali, N.; Dias, A.G.; Lopes, M.A.; Santos, J.D.; Buddhudu, S. (Thin Solid FilmsThin Solid Films, 2006)
This paper reports on the affect of lead content on the absorption and emission spectra of the Ho 3+ ion doped lead-zinc-borate glasses in the composition (mol%) of (20 - x)PbO-20ZnO-(59 + x)B 2O 3-1.0Ho 2O 3 where x = 0, 5,10,15 of PbO content with λ exc = 405 nm. The experimental absorption band energies have satisfactorily been correlated with the theoretical results with an r.m.s deviation of zero with the following correction factors obtained by a least square fit analysis: ΔE 1 = 348.495936 cm
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2005.12.085Language of Original Document: EnglishCorrespondence Address: Sooraj Hussain, N.; DEMM, Faculty of Eng. University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: sooraj@fe.up.ptReferences: Song, J.H., Jong Heo, Park, S.H., (2003) J. Appl. Phys., 93, p. 9441;Chen, Q., Ferraris, M., Menke, Y., Milanese, D., Monchiero, E., (2003) J.Non-Cryst. Solids, 324, p. 1; Kassab, L.R.P., Courrol, L.C., Morais, A.S., Mendes, C.M.S.P., Tatumi, S.H., Wetter, N.U., Gomes, L., Salvador, V.L.R., (2002) J.Non-Cryst. Solids, 304, p. 233; Kityk, I.V., Wasylak, J., Kucharski, J., Dorosz, D., (2002) J .Non-Cryst. Solids, 297, p. 285; Souza Filho, A.G., Mendes Filho, J., Melo, F.E.A., Custodio, M.C.C., Lebullenger, R., Hernandes, A.C., (2000) .J. Phys. Chem. Solids, 61, p. 1535; Choi, Y.G., Jong Heo, (1997) J. Non-Cryst. Solids, 217, p. 199; Koepke, Cz., Wisniewski, K., Sikorski, L., Piatkowski, D., Kowalska, K., Naftaly, M., (2006) Opt. Mater., 28, p. 129; Szachowicz, M., Tascu, S., Joubert, M.-F., Moretti, P., Nikl, M., (2006) Opt. Mater., 28, p. 162; Kassab, L.R.P., de Oliveira Preto, A., Lozano, W., de Sá, F.X., Maciel, G.S., (2005) J. Non-Cryst. Solids, 351, p. 3468; Lavín, V., Lahoz, F., Martín, I.R., Rodríguez-Mendoza, U.R., Cáceres, J.M., (2005) Opt. Mater., 27, p. 1754; Karmakar, B., (2005) J. Solid State Chem., 178, p. 2663; Pisarski, W.A., Goryczka, T., Wodecka-Duś, B., Płońska, M., Pisarska, J., (2005) Mater. Sci. Eng., 122, p. 94; Speghini, A., Peruffo, M., Casarin, M., Ajo, D., Bettinelli, M., (2000) J. Alloys Comp., 300-301, p. 174; Fermi, F., Ingletto, G., Aschieri, C., Bettinelli, M., (1989) Inorg. Chim. Acta, 163, p. 123; Ingletto, Bettinelli, M., Di Sipio, L., Negrisolo, F., Aschieri, C., (1991) Inorg. Chim. Acta, 188, p. 201; Saisudha, M.B., Ramakrishna, J., (1996) Phys. Rev., B, 53, p. 6186; Zahara, A.-M., Zahra, C.Y., (1993) J. Non-Cryst. Solids, 155, p. 45; Motke, S.G., Yawale, S.P., Yawale, S.S., (2002) Bull. Mater. Sci., 25, p. 75; Peres, T., Litton, D.A., Capobianco, J.A., Garofalini, S.H., (1997) J. Non-Cryst. Solids, 221, p. 34; Reddy, M.R., Raju, S.B., Veeraiah, N., (2000) J. Phys. Chem. Solids, 61, p. 1567; Prasad, N.V.V., Annapurna, K., Sooraj Hussain, N., Buddhudu, S., (2003) Mater. Lett., 57, p. 2071; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2001) Mater. Lett., 48, p. 303; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2002) Spectrosc. Lett., 35 (2), p. 275; Sooraj Hussain, N., Prabhakara Reddy, Y., Rajamohan Reddy, K., Buddhudu, S., (2001) Phys. Chem. Glasses, 42 (6), p. 358; Sooraj Hussain, N., Annapurna, K., Prabhakara Reddy, Y., Buddhudu, S., (2002) J. Mater. Sci. Lett., 21, p. 397; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2001) Mater. Res. Bull., 36, p. 1813; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2002) Mater. Lett., 52, p. 429; Lakshminarayana, G., Buddhudu, S., (2005) Spectrochim. Acta, A, 62, p. 364; Judd, B.R., (1962) Phys. Rev., 127, p. 750; Ofelt, G.S., (1962) J. Chem. Phys., 37, p. 511; Weber, M.J., Matsinger, B.H., Domlan, V.L., Surratt, G.T., (1972) J. Chem. Phys., 57, p. 562; Rukmini, E., Jayasankar, C.K., (1995) Opt. Mater., 4, p. 529; Auzel, F., (1987) Spectroscopy of Solid State Lase-Type Materials, , Di Bartolo B. (Ed), Plenum, New York; Guery, C., Adam, J.L., Lucas, J., (1987) J. Lumin., 42, p. 266; Shelby, J.E., Ruller, J., (1987) Phys. Chem. Glasses, 28, p. 262; Wong, E.Y., (1961) J. Chem. Phys., 35, p. 544; Wong, E.Y., (1963) J. Chem. Phys., 38, p. 976; Hufner, S., (1978) Optical Spectra of Transparent Rare-Earth Compounds, , Academic Press, New York; Jorgensen, C.K., (1962) Orbitals in Atoms and Molecules, , Academic Press, London; Sinha, S.P., (1966) Complexes of Rare-Earths, , Pergamon Press, Oxford; Rao, T.V.R., Reddy, R.R., Nazeer Ahammed, Y., Parandamaiah, M., Sooraj Hussain, N., Buddhudu, S., Purandar, K., (2000) Infrared Phys. Technol., 41, p. 247; Weber, M.J., Ziegler, D.C., Angell, C.A., (1982) J. Appl. Phys., 53, p. 4344; Rai, S.B., (2002) Spectrochim. Acta, A, 58, p. 1559; Rakov, N., Maciel, G.S., de Araujo, C.B., Messaddeq, Y., (2002) J. Appl. Phys., 91, p. 1272; Villacampa, B., Orera, V.M., Merino, R.I., Cases, R., Alonso, P.J., Alcalá, R., (1991) Mater. Res. Bull., 26, p. 741; Weber, M.J., Matsinger, B.H., Donlan, V.L., Surratt, G.T., (1972) J. Chem. Phys., 57, p. 562; Quagliano, J.R., Richardson, F.S., Reid, M.F., (1992) J. Alloys Compd., 180, p. 131; McDugall, J., Hollis, D.B., Payne, M.J.P., (1994) Phys. Chem. Glasses, 35, p. 258; Cases, R., Chamarro, M.A., (1991) J. Solid State Chem., 90, p. 313
Keywords: Band energies; Doping (additives); Energy gap; glass; Glasses; Holmium; Holmium glasses; Light absorption; Luminescence; Luminescences; Luminescent transitions; Optical properties; Stimulated emission

Adsorption of albumin on prosthetic materials: Implication for tribological behavior - Serro, A.P.; Gispert, M.P.; Martins, M.C.L.; Brogueira, P.; Colaço, R.; Saramago, B. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The orthopedic prosthesis used to substitute damaged natural joints are lubricated by a pseudosynovial fluid that contains biological macromolecules with potential boundary lubrication properties. Proteins are some of those macromolecules whose role in the lubrication process is not yet completely understood. In a previous work, we investigated the influence of the presence of albumin, the major synovial protein, upon the tribological behavior of three of the most used pairs of artificial joint materials: ultra high molecular weight polyethylene (UHMWPE) against counterfaces of alumina, CoCrMo alloy, and 316L stainless steel. Albumin was found to cause a significant decrease in the friction coefficient when the counterfaces were metallic because transfer of UHMWPE was avoided, but this effect was much weaker in the case of alumina. The objective of the present work was to look for an explanation for these differences in tribological behavior in terms of albumin adsorption. With this goal, studies on adsorption of bovine serum albumin (BSA) on the counterface materials, from a biological model fluid (Hanks' balanced salt solution), were carried out using radiolabeled albumin ( 125I-BSA), X-ray photoelectron spectroscopy, and atomic force microscopy. The conclusion from all techniques is that the driving force for albumin adsorption is higher on the metals than on alumina. These results confirm that the greater the amount of protein adsorbed on the counterface, the more efficient is the protection against the transfer of polymeric film to the counterface. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30754PubMed ID: 16739106Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Química Estrutural, Instituto Superior Técnico, Av. Rovisco Pais, 1049-001 Lisboa, Portugal; email: anapaula.serro@ist.utl.ptChemicals/CAS: aluminum oxide, 1302-74-5, 1318-23-6, 1344-28-1, 14762-49-3; iodine 125, 14158-31-7, 22822-81-7; molybdenum, 7439-98-7; protein, 67254-75-5; stainless steel, 12597-68-1; Albumins; Biocompatible MaterialsTradenames: CHIRULEN, Poly Hi Solidur, GermanyManufacturers: Maret, Switzerland; MediMet, Germany; Poly Hi Solidur, GermanyReferences: Widmer, M.R., Heuberger, M., Vörös, J., Spencer, N.D., Influence of polymer surface chemistry on frictional properties under protein-lubrication conditions: Implications for hip-implant design (2001) Tribol Lett, 10, pp. 111-116;Saikko, V., Effect of lubricant protein concentration on the wear of ultrahigh molecular weight polyethylene sliding against a CoCr counterface (2003) Trans ASME, 125, pp. 638-642; Sawae, Y., Murakami, T., Chen, J., Effect of synovia constituents on friction and wear of ultra-high molecular weight polyethylene sliding against prosthetic joint materials (1998) Wear, 216, pp. 213-219; Kumar, P., Oka, M., Ikeuchi, K., Shimizu, K., Yamamuro, T., Okumura, H., Kotoura, Y., Low wear rate of UHMWPE against zirconia ceramic (Y-PSZ) in comparison to alumina ceramic and SUS 316L alloy (1991) J Biomed Mater Res, 25, pp. 813-828; Kitano, T., Ateshian, G.A., Mow, V.C., Kadoya, Y., Yamano, Y., Constituents and pH changes in protein rich hyaluronan solution affect the biotribological properties of artificial cartilage (2001) J Biomech, 34, pp. 1031-1037; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., Friction and wear mechanisms in hip prosthesis: Comparison of joint materials behaviour in several lubricants (2006) Wear, 260, pp. 149-158; Van Enckevort, H.J., Dass, D.V., Langdon, A.G., The adsorption of bovine serum albumin at the stainless-steel/aqueous solution interface (1984) J Colloid Interface Sci, 98, pp. 138-143; Fukuzaki, S., Urano, H., Nagata, K., Adsorption of protein onto stainless-steel surfaces (1995) J Ferment Bioeng, 80, pp. 6-11; Rubio, C., Costa, D., Bellon-Fontaine, M.N., Relkin, P., Pradier, C.M., Marcus, P., Characterization of bovine serum albumin adsorption on chromium and AISI 304 stainless steel, consequences for the Pseudomonas fragi K1 adhesion (2002) Colloid Surf B Biointerface, 24, pp. 193-205; Sakiyama, T., Tomura, J., Imamura, K., Nakanishi, K., Adsorption characteristics of bovine serum albumin and its peptide fragments on a stainless steel surface (2004) Colloid Surf B Biointerface, 33, pp. 77-84; Fukuzaki, S., Urano, H., Yamaguchi, T., Effect of modification of alumina surfaces by ozone on adsorption behaviour of bovine serum albumin at alumina-water interfaces (1997) J Ferment Bioeng, 84, pp. 407-413; Urano, H., Fukuzaki, S., Conformation of adsorbed bovine serum albumin governing its desorption behavior at alumina-water interfaces (2000) J Ferm Bioeng, 90, pp. 105-110; Williams, R.L., Williams, D.F., Albumin adsorption on metal surfaces (1998) Biomaterials, 9, pp. 206-212; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Colloid Surf B Biointerface, 2, pp. 517-566; Owens, D.K., Wendt, R.C., Estimation of the surface free energy of polymers (1969) J Appl Polym Sci, 13, pp. 1741-1747; Michalski, M.C., Hardy, J., Saramago, B., On the surface tension of PVC/EVA polymer blends: Comparison of different calculation methods (1998) J Colloid Interface Sci, 208, pp. 319-328; Cheng, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation zof axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Colloid Surf, 43, pp. 151-197; Cheng, P., Neumann, A.W., Computational evaluation of Axisymmetric Drop Shape Analysis - Profile (ADSA-P) (1992) Colloid Surf, 62, pp. 297-306; (1990) Practical Surface Analysis, Vol. 1: Auger and X-Ray Photoelectron Spectroscopy, 1. , Briggs D, Seah MP, editors. Cichester: Wiley; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125, a Guide to Radioiodination Techniques, p. 64. , Little Chalfont, Buckinghamshire, UK: Amersham Life Science; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isotherms, competitivity, desorption and exchange of albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333; Paynter, R.W., Ratner, B.D., Horbett, T.A., Thomas, H.R., XPS studies on the organization of adsorbed protein films on fluoropolymers (1984) J Colloid Interface Sci, 101, pp. 233-245; Paynter, R.W., Ratner, B.D., The study of interfacial proteins and biomolecules by X-ray photoelectron spectroscopy (1985) Surface and Interfacial Aspects of Biomedical Polymers, Vol. 2: Protein Adsorption, 2, pp. 189-216. , Andrade JD, editor. New York: Plenum; Seah, M.P., Dench, W.A., Quantitative electron spectroscopy of surfaces: A standard data base for electron inelastic mean free paths in solids (1979) Surf Interface Anal, 1, pp. 2-11; Tanuma, S., Powell, C.J., Penn, D.R., Calculations of electron inelastic mean free paths. II. Data for 27 elements over the 50-2000 eV range (1991) Surf Interface Anal, 17, pp. 911-926; Carter, D.C., He, X.M., Munson, S.H., Twigg, P.D., Gernet, K.M., Broom, M.B., Miller, T.Y., Three-dimensional structure of human serum albumin (1989) Science, 244, pp. 1195-1198; Pradier, C.M., Costa, D., Rubio, C., Compère, C., Marcus, P., Role of salts on BSA adsorption on stainless steel in aqueous solutions. I. FT-IRRAS and XPS characterization (2002) Surf Interface Anal, 34, pp. 50-54; Lori, J.A., Hanawa, T., Adsorption characteristics of albumin on gold and titanium metals in Hanks' solution using EQCM (2004) Spectroscopy, 18, pp. 545-552; Sousa, S.R., Moradas-Ferreira, P., Saramago, B., Melo, L.V., Barbosa, M.A., Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma (2004) Langmuir, 20, pp. 9745-9754; Uyen, H.M.W., Schakenraad, J.M., Sjollema, J., Noordmans, J., Jongebloed, W.L., Stokroos, I., Busscher, H.J., Amount and different surface structure of albumin adsorbed to solid substrata with different wettabilities in a parallel plate flow cell (1990) J Biomed Mater Res, 24, pp. 1599-1614; Young, B.R., Pitt, W.G., Cooper, S.L., Protein adsorption on polymeric biomaterials. II. Adsoption kinetics (1988) J Colloid Interface Sci, 125, pp. 246-260; Dulm, P.V., Norde, W., The adsorption of human plasma albumin on solid surfaces, with special attention to the kinetic aspects (1983) J Colloid Interface Sci, 91, pp. 248-255; Malmsten, M., Formation of adsorbed protein layers (1998) J Colloid Interface Sci, 207, pp. 186-199; Smith, I.O., Baumann, M.J., McCabe, L.R., Electrostatic interactions as a predictor for osteoblast attachment to biomaterials (2004) J Biomed Mater Res A, 70, pp. 436-441
Keywords: Adsorption; Albumin; Albumin adsorption; Albumins; Alumina; aluminum oxide; article; Atomic force microscopy; balanced salt solution; Biocompatible Materials; Body fluids; bovine serum albumin; chromium derivative; Cobalt alloy; Cobalt alloys; cobalt derivative; force; Friction; iodine 125; isotope labeling; joint fracture; Joints (anatomy); lubrication; macromolecule; metal; molecular weight; molybdenum; orthopedic prosthesis; orthopedics; Polyethylenes; polymer; Prostheses and Implants; prosthesis material; Prosthetics; protein; Proteins; Pseudosynovial fluid; Stainless steel; Thermodynamics; Tribology; ultra high molecular weight polyethylene; Ultra high molecular weight polyethylene (UHMWPE); X ray photoelectron spectroscopy

Assessment of Bonelike® graft with a resorbable matrix using an animal model - Lobato, J.V.; Hussain, N.S.; Botelho, C.M.; Maurício, A.C.; Afonso, A.; Ali, N.; Santos, J.D. (Thin Solid FilmsThin Solid Films, 2006)
Synthetic bone grafts have been developed to provide an alternative to autografts and allografts. Bonelike® is a patented synthetic osteoconductive bone graft that mimics the mineral composition of natural bone. In the present preliminary animal studies a user-friendly version of synthetic bone graft Bonelike® have been developed by using a resorbable matrix, Floseal®, as a vehicle and raloxifene hydrochloride as a therapeutic molecule, that is known to decrease osteoclast activity and therefore enhanced bone formation. From histological and scanning electron microscopy evaluations, the use of Bonelike® associated with Floseal® and raloxifene hydrochloride showed that new bone was rapidly apposed on implanted granules and also that the presence of the matrix and therapeutic molecule does not alter the proven highly osteoconductivity properties of Bonelike®. Therefore, this association may be one step-forward for the clinical applications of Bonelike® scaffolds since it is much more easy-to-handle when compared to granular materials. © 2006 Elsevier B.V. All rights reserved.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2005.12.153Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, Singapore, , Scientific W. (Ed);Hench, L.L., (1998) Biomaterials, 19, p. 1419; Giannoudis, P.V., Dinopoulos, H., Tsiridis, E., (2005) Injury, 36 S, pp. S20; Murugan, R., Ramakrishma, S., (2005) Compos. Sci. Technol., 65, p. 2385; Ewers, R., Simons, B., (1992) Biomaterials-Hard tissue repair and replacement, pp. 67-80. , Elsiever, The Netherlands; Ilan, D.I., Ladd, A.L., (2002) Oper. Tech. Plast. Reconstr. Surg., 9, p. 151; Mary, E.A.R., Raymond, A.Y., (1998) Dent. Clin. North Am., 42, p. 491; Keating, J., McQueen, M., (2001) J. Bone Jt. Surg., 83 B, p. 3; Summers, B.M., Eisenstein, S.M., (2001) J. Bone Jt. Surg., 71 B, p. 677; Younger, E.M., Chapman, M.W., (1989) J. Orthop. Trauma, 3, p. 192; LeGeros, R.Z., (2002) Clin. Orthop. Res., 395, p. 81; Daculsi, G., (1998) Biomaterials, 19, p. 1473; Bohner, M., van Lenthe, G.H., Grunenfelder, S., Hirsiger, W., Evison, R., Muller, R., (2005) Biomaterials, 26, p. 6099; LeGeros, R.Z., (1981) Prog. Cryst. Growth Charact., 1-2, p. 1; LeGeros, R.Z., (1993) Dense Hydroxyapatite, An Introduction to Bioceramics, , World Scientific, Singapore; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 21, p. 749; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Oslen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Mathiasen, R.A., Cruz, R.M., (2004) Otolaryngol. Head Neck Surg., 131, p. 601; User, H.M., Robert, B.N., (2003) Urology, 62, p. 342; Kheirabadi, B.S., Field-Redley, A., Pearson, R., MacPhee, M., Drohan, W., Tuthill, D., (2002) J. Surg. Res., 106, p. 99; Gill, I.S., Ramani, A.P., Spaliviero, M., Xu, M., Finelli, A., Kaouk, J.H., Desai, M.M., (2005) Urology, 65, p. 463; Weaver, F.A., Hood, D.B., Zatina, M., Messina, L., Badduke, B., (2002) Ann. Vasc. Surg., 16, p. 286; Ettinger, B., Genant, H.K., Cann, C.E., (1985) Ann. Intern. Med., 102, p. 319; Manolagas, S., Kousteni, S., Jilka, R., (2002) Recent Prog. Horm. Res., 57, p. 385; Trontelj, J., Vovk, T., Bogataj, M., Mrhar, A., (2005) Pharmacol. Res., 52, p. 334; Bryant, H., Glasebrook, A.L., Yang, N.N., Sato, M., (1999) J. Steroid Biochem. Mol. Biol., 69, p. 37; Bjarnason, N.H., Haarbo, J., Byrjalsen, I., Alexandersen, P., Kauffman, R.F., Christiansen, C., (2001) Atherosclerosis, 154, p. 97; Somjen, D., Yoles, I., (2003) J. Steroid Biochem. Mol. Biol., 86, p. 93; Buelke-Sam, J., Bryant, H.U., Francis, P.C., (1998) Reprod. Toxicol., 12, p. 217; Black, L.J., Sato, M., Rowley, E.R., Magee, D.E., Bekele, A., Williams, D.C., Cullinan, G.J., Bryant, H.U., (1994) J. Clin. Invest., 93, p. 63; Delmas, P.D., Bjarnason, N.H., Mitlak, B.H., Ravoux, A.C., Shah, A.S., Huster, W.J., Draper, M., Christiansen, C., (1997) N. Engl. J. Med., 337, p. 1641; Lobato, J.V., Sooraj Hussain, N., Botelho, C.M., Rodrigues, J.M., Luis, A.L., Mauricio, A.C., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 877; Gutierres, M., Sooraj Hussain, N., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 1041; Costa, M.A., Gutierres, M., Almeida, L., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Eng. Mater., 254-256, p. 821; Duarte, F.M., Santos, J.D., Afonso, A., (2004) Mat. Sci. Forum, 455-456, p. 370; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology a Text and Atlas, New York
Keywords: animal model; Bone; Bonelike®; FloSeal®; Grafting (chemical); Histological analysis; Mathematical models; Raloxifene hydrochloride; Scanning electron microscopy

Calcium phosphate microspheres for localised delivery of a therapeutic enzyme - Barrias, C.C.; Ribeiro, C.C.; Martins, M.C.L.; Barbosa, M.A.; Rodrigues, D.; Miranda, M.C.S. (Key Engineering MaterialsKey Eng Mat, 2006)
The ability of calcium titanium phosphate (CTP) and hydroxyapatite (HAp) microspheres to reversibly adsorb the enzyme glucocerebrosidase (GCR) while preserving its biological activity, and efficiently deliver it to Gaucher disease (GD) fibroblasts was investigated. CTP microspheres adsorbed ca. 3.6-fold more GCR than HAp microspheres. The activity of adsorbed GCR was higher than the free enzyme in the case of CTP microspheres and lower when HAp was used. GCR release from both types of microspheres was characterized by the initial elution of a large percentage of enzyme followed by a delayed release that extended for at least 30 days. Released GCR was internalized by GD fibroblasts increasing their intracellular enzymatic activity. In cells treated with the same amount of GCR-loaded CTP microspheres or free-GCR a higher intracellular activity was detected in the former case, suggesting an improved efficacy.
Keywords: Adsorption; Biocompatibility; biological activity; Biomaterials; Calcium Compounds; Calcium titanium phosphate; Calcium titanium phosphate (CTP); Cells; Enzyme adsorption; Enzymes; hydroxyapatite; Microspheres

Cellulose phosphates as biomaterials. In vitro biocompatibility studies - Granja, P.L.; Jéso, B.D.; Bareille, R.; Rouais, F.; Baquey, C.; Barbosa, M.A. (Reactive and Functional PolymersReact Funct Polym, 2006)
Grafting of phosphate groups has been investigated as a means to render biomedical polymers able to induce the formation of an apatite layer. In the present investigation, regenerated cellulose hydrogels were surface modified by phosphorylation using a previously reported method. The in vitro biocompatibility of materials with varying phosphate contents was evaluated in cultured human bone marrow stromal cells (HBMSC), in terms of cytotoxicity, cell attachment, proliferation and immunohistochemistry. Negatively charged cellulose phosphates were neutralized in the form of the calcium salt before contact with cells. Cellulose phosphates were not cytotoxic, independently of the phosphate content. Unmodified regenerated cellulose hydrogels showed good rates of HBMSC attachment and proliferation. On the contrary, negatively charged, highly hydrophilic, phosphorylated surfaces showed poor HBMSC attachment and proliferation, as well as poor alkaline phosphatase-specific activity and expression of osteocalcin and type I collagen. Differences found are discussed in terms of surface chemical functionality, hydrophilicity and charge. © 2005 Elsevier B.V. All rights reserved.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: RFPOFdoi: 10.1016/j.reactfunctpolym.2005.10.027Language of Original Document: EnglishCorrespondence Address: Granja, P.L.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: pgranja@ineb.up.ptReferences: Albrektsson, T., (1998) Handbook of Biomaterial Properties, p. 500. , Black J., and Hastings G. (Eds), Chapman & Hall, London;Friedman, R.J., Black, J., Galante, J.O., Jacobs, J.J., Skinner, H.B., (1993) J. Bone Joint. Surg., 75 A, p. 1086; Puleo, D.A., Nanci, A., (1999) Biomaterials, 20, p. 2311; Lamba, N.M.K., Baumgartner, J.A., Cooper, S.L., (1998) Frontiers in Tissue Engineering, p. 121. , Patrick C.W., Mikos A.G., and McIntire L.V. (Eds), Elsevier, Amsterdam; Horbett, T.A., (2004) Biomaterials Science: An Introduction to Materials in Medicine. second ed., p. 237. , Ratner B.D., Hoffman A.S., Schoen F.J., and Lemons J.E. (Eds), Elsevier-Academic Press, San Diego; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., (1999) J. Biomed. Mater. Res., 44, p. 1; Lee, J.H., Lee, H.B., (1993) J. Biomater. Sci. Polym. Ed., 4, p. 467; Healy, K.E., Thomas, C.H., Rezania, A., Kim, J.E., McKeown, P.J., Lom, B., Hockberger, P.E., (1996) Biomaterials, 17, p. 195; Vogler, E.A., (1993) Surfactant Science Series, 49, p. 183. , Berg J.C. (Ed), Marcel Dekker, New York (Wettability); Choee, J.H., Lee, S.J., Lee, Y.M., Rhee, J.M., Lee, H.B., Khang, G., (2004) J. Appl. Polym. Sci., 92, p. 599; Faucheux, N., Schweiss, R., Lutzow, K., Werner, C., Groth, T., (2004) Biomaterials, 25, p. 2721; Webb, K., Hlady, V., Tresco, P.A., (1998) J. Biomed. Mater. Res., 41, p. 422; De Rosa, M., Carteni, M., Petillo, O., Calarco, A., Margarucci, S., Rosso, F., De Rosa, A., Peluso, G., (2004) J. Cell. Physiol., 198, p. 133; Habbaba, M.M., Ulgen, K.O., (1997) J. Chem. Technol. Biotechnol., 69, p. 405; Lee, J.H., Lee, J.W., Khang, G., Lee, H.B., (1997) Biomaterials, 18, p. 351; Keselowsky, B.G., Collard, D.M., Garcia, A.J., (2004) Biomaterials, 25, p. 5947; Webb, K., Hlady, V., Tresco, P.A., (2000) J. Biomed. Mater. Res., 49, p. 362; Smetana Jr., K., (1993) Biomaterials, 14, p. 1046; Jayaraman, M., Meyer, U., Buhner, M., Joos, U., Wiesmann, H.P., (2004) Biomaterials, 25, p. 625; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res., 49, p. 155; von Recum, A.F., Brown, C.E., Shannon, C.E., LaBerge, M., (1999) Handbook of Biomaterials Evaluation: Scientific, Technical and Clinical Testing of Implant Materials. second ed., p. 227. , von Recum A.F. (Ed), Edwards Brothers, Ann Arbor; Hon, D.N.-S., (1996) Polysaccharides in Medicinal Applications, p. 87. , Dumitriu D. (Ed), Marcel Dekker, New York; Franz, G., (1986) Adv. Polym. Sci., 76, p. 1; Ikada, Y., (1989) Cellulose: Structural and Functional Aspects, p. 447. , Kennedy J.F., Phillips G.O., and Williams P.A. (Eds), Ellis Horwood, Chichester; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., Noishiki, Y., (1989) J. Biomed. Mater. Res., 23, p. 125; Dias, G.J., Peplow, P.V., Teixeira, F., (2003) J. Mater. Sci.: Mater. Med., 14, p. 739; Uysal, A., Ozbek, S., Ozcan, M., (2003) Plast. Reconstr. Surg., 112, p. 540; Galgut, P.N., (1990) Biomaterials, 11, p. 561; Skoog, T., (1967) Scand. J. Plast. Reconstr. Surg., 1, p. 113; Chauveaux, D., Barbie, C., Barthe, X., Baquey, C., Poustis, J., (1990) Clin. Mater., 5, p. 251; Poustis, J., Baquey, C., Chauveaux, D., (1994) Clin. Mater., 16, p. 119; Li, S., Liu, Q., de Wijn, J., Wolke, J., Zhou, B., de Groot, K., (1997) J. Mater. Sci.: Mater. Med., 8, p. 543; Mucalo, M.R., Yokogawa, Y., Toryiama, M., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., (1995) J. Mater. Sci.: Mater. Med., 6, p. 597; Mucalo, M.R., Yokogawa, Y., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., (1995) J. Mater. Sci.: Mater. Med., 6, p. 658; Granja, P.L., Pouységu, L., Pétraud, M., De Jéso, B., Baquey, C., Barbosa, M.A., (2001) J. Appl. Polym. Sci., 82, p. 3341; Granja, P.L., Pouységu, L., Deffieux, D., Daudé, G., De Jéso, B., Labrugère, C., Baquey, C., Barbosa, M.A., (2001) J. Appl. Polym. Sci., 82, p. 3354; Granja, P.L., Barbosa, M.A., Pouységu, L., De Jéso, B., Baquey, C., (1999) Frontiers in Biomedical Polymers Applications, 2, p. 195. , Ottenbrite R. (Ed), Technomic Press, Lancaster; Granja, P.L., Pouységu, L., De Jéso, B., Rouais, F., Baquey, C., Barbosa, M.A., (2001) J. Mater. Sci., 36, p. 2163; Kim, S.S., Jeong, W.Y., Shin, B.C., Oh, S.Y., Kim, H.W., Rhee, J.M., (1998) J. Biomed. Mater. Res., 40, p. 401; Saito, T., Arsenault, A.L., Yamauchi, M., Kuboki, Y., Crenshaw, M.A., (1997) Bone, 21, p. 305; van den Bos, T., Beertsen, W., (1994) J. Bone Min. Res., 9, p. 1205; Linde, A., (1992) Calcification in Biological Systems, p. 269. , Bonucci E. (Ed), CRC Press, Boca Raton; Veis, A., Sharkey, M., Dickson, I., (1977) Calcium Binding Proteins and Calcium Function, p. 408. , Wasserman R.H. (Ed), Elsevier, New York; Vilamitjana-Amédée, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., (1993) In Vitro Cell. Dev. Biol., 29 A, p. 699; Mosmann, T., (1983) J. Immunol. Meth., 65, p. 55; Dumitriu, S., Dumitriu, M., (1996) Polysaccharides in Medicinal Applications, p. 705. , Dumitriu S. (Ed), Marcel Dekker, New York; Van Blitterswijk, C.A., Bakker, D., Hesseling, S.C., Koerten, H.K., (1991) Biomaterials, 12, p. 187; Curtis, A.S.G., Forrester, J.V., Clark, P., (1986) J. Cell. Sci., 86, p. 9; Katayama, Y., House, C.M., Udagawa, N., Kazama, J.J., McFarland, R.J., Martin, T.J., Findlay, D.M., (1998) J. Cell. Physiol., 176, p. 179; Boskey, A.J., (1995) Ann. N. Y. Acad. Sci., 760, p. 249; Yamamoto, M., Kato, K., Ikada, Y., (1997) J. Biomed. Mater. Res., 37, p. 29; Alliot-Licht, B., Gregoire, M., Orly, I., Menanteau, J., (1991) Biomaterials, 12, p. 752; Oreffo, R.O.C., Driessens, F.C.M., Planell, J.A., Triffitt, J.T., (1998) Biomaterials, 19, p. 1845; Sun, J.-S., Tsuang, Y.-H., Liao, C.-J., Liu, H.-C., Hang, Y.-S., Lin, F.-H., (1997) J. Biomed. Mater. Res., 37, p. 324; Padilha, P.M., Tocha, J.C., Moreira, J.C., Campos, J.T.S., Federici, C.C., (1997) Talanta, 41, p. 317; Mizusawa, Y., Burke, J.R., (1996) J. Pediatr. Child. Health, 32, p. 350; Anwar, M., Krishnamoorthy, S., (1987) Indian J. Text. Res., 12, p. 24; Hoffman, A.S., (2004) Biomaterials Science: An Introduction to Materials in Medicine. second ed., p. 107. , Ratner B.D., Hoffman A.S., Schoen F.J., and Lemons J.F. (Eds), Elsevier-Academic Press, San Diego
Keywords: Biocompatibility; Biomaterials; Cell attachment; Cell culture; Cellulose; Cellulose derivatives; Cellulose phosphates; Cytotoxicity; Grafting (chemical); Human bone marrow stromal cells; Hydrogels; hydrophilicity; immunohistochemistry; In vitro; Phosphorylation; Proliferation; Regenerated cellulose hydrogels; toxicity

Characterization of fetal heart rate irregularity using approximate entropy and wavelet filtering - Magalhães, F.; Marques De Sá, J.P.; Bernardes, J.; Ayres-de-Campos, D. (Computers in CardiologyComput Cardiol, 2006)
Approximate Entropy (ApEn) has been used by several researchers as a means to characterize the irregularity of fetal heart rate (FHR), a major contributor to fetal risk assessment. The present work starts by analyzing the influence of accelerative and decelerative (AD) components of the FHR signal in the computation of ApEn. Having shown that the AD components may completely distort the ApEn evaluation we proceed to present two methods of eliminating the influence of the AD components: wavelet filtering; AD detection using specific algorithms based on well-established physiological criteria. We obtained good results with the first method when applied to simulated signals; however it proved unreliable in the practical application of discriminating normal from pathological fetal FHR. With the second method we were able to achieve this discrimination with high statistical significance.
Conference code: 73228Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusArt. No.: 4512006CODEN: COCADLanguage of Original Document: EnglishCorrespondence Address: Marques De Sá, J. P.; Faculdade de Engenharia, DEEC, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jmsa@fe.up.ptReferences: Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc. Natl. Acad. Sci. U.S.A, 88, pp. 2297-2301;Pincus, S., Randomness and degrees of irregularity (1996) Proc. Natl. Acad. Sci. U.S.A, 93, pp. 2083-2088; Pincus, S.M., Viscarello, R.R., Approximate entropy: A regularity measure for fetal heart rate (1992) Obstet. Gynecol, 2, pp. 249-255; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin. Sci, 4, pp. 345-349; van Leeuwen, P., Lange, S., Betterman, H., Gronemeyer, D., Hatzmann, W., Fetal heart rate variability and complexity in the course of pregnancy (1999) Early Human Develop, 54, pp. 259-269; Pincus, S., Assessing Serial Irregularity and its Implications for Health (2001) Ann N Y Acad Sci, 954, pp. 245-267; Cysarz, D., Betterman, H., van Leeuwen, P., Entropies of short binary sequences in heart period dynamics (2000) Am J Physiol Heart Circ Physiol, 6, pp. 2163-2172; Signorini, M.G., Magenes, G., Cerutti, S., Arduini, D., Linear and Nonlinear Parameters for the Analysis of Fetal Heart Rate Signal from Cardiotocographic Recordings (2003) IEEE Tr. BME, 50, pp. 365-373; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J., Pereira-Leite, L., SisPorto 2.0 - A Program for Automated Analysis of Cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Sá Couto, P.M., van Meurs, W.L., Bernardes, J.F., Marques de, S.J., Goodwin, J.A., Combined Model-Driven and Rule-Based Approach for Educational Simulation of Fetal Heart Rate (2002) Proc. 16th Biennial Int. Conf. Europ. Assoc. for Speech, Signal and Image Processing, pp. 400-402. , EURASIP, Brno, Czech Rep, pp; Marques de Sá, J.P., Characterization of fetal heart rate using approximate entropy (2005) Proc. IEEE Comp. in Cardiology 2005, 32, pp. 671-673
Keywords: Approximate entropy; Cardiology; Fetal heart rate; Neonatal monitoring; Occupational risks; Physiological models; risk assessment; Risk management; Safety engineering; Simulated signals; Statistical significance; Wavelet filtering

The class imbalance problem in TLC image classification - Sousa, A.V.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
The paper presents the methodology developed to solve the class imbalanced problem that occurs in the classification of Thin-Layer Chromatography (TLC) images. The proposed methodology is based on resampling, and consists in the undersampling of the majority class (normal class), while the minority classes, which contain Lysosomal Storage Disorders (LSD) samples, are oversampled with the generation of synthetic samples. For image classification two approaches are presented, one based on a hierarchical classifier and another uses a multiclassifier system, where both classifiers are trained and tested using balanced data sets. The results demonstrate a better performance of the multiclassifier system using the balanced sets. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68310Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto Superior de Engenharia do Porto, Rua Dr. Antonio Bernardino de A. 431, 4200-072 Porto, Portugal; email: ats@isep.ipp.ptReferences: Kubat, M., Holte, R., Matwin, S., Learning when negative examples abound (1997) European Conference on Machine Learning, pp. 146-153;Lazarević, A., Srivastava, J., Kumar, V., Data mining for analysis of rare events: A case study in security, financial and medical applications (2004) PAKDD-2004; Skurichina, M., Raudys, S., Duin, R.P.W., K-nearest neighbors directed noise injection in multilayer perceptron training (2000) IEEE Transactions on Neural Networks, 11 (2); Chawla, N.V., Japkowicz, N., Kolcz, A., Editorial: Special issue on learning from imbalanced data sets (2004) Sigkdd Explorations, 6 (1), pp. 1-6; Japkowicz, N., Class imbalances: Are we focusing on the right issue? Workshop on Learning from Imbalanced Datasets II, p. 6. , (2003) ICML, Washington DC; Chawla, N.V., Lazarević, A., Hall, L.O., Bowyer, K.W., SMOTEBoost: Improving the prediction of minority class in boosting (2003) 7th European Conference on Principles and Practice of Knowledge Discovery in Databases (PKDD), pp. 107-119; Domingos, P., MetaCost: A general method for making classifiers cost-sensitive (1999) Conference on Knowledge Discovery in Data Proceedings of the Fifth ACM SIGKDD International Conference on Knowledge Discovery and Data Mining, pp. 155-164; Fan, W., Stolfo, S., Zhang, J., Chan, P., Adacost: Misclassication cost-sensitive boosting (1999) Proceedings of Sixteenth International Conference on Machine Learning, pp. 983-990; Tax, D.M.J., One-class classification; Concept-learning in the absence of counterexamples (2001) ASCI Dissertation Series, 65, pp. 1-190. , PhD thesis Delft University of Technology; Ridder, D., Tax, D.M.J., Duin, R.P.W., An experimental comparison of one-class classification methods (1998) Proc ASCI'98, 4th Annual Conf of the Advanced School for Computing and Imaging, pp. 213-218. , (Lommel, Belgium, June 9-11), ASCI, Delft; Lazarevic, A., Ertoz, L., Ozgur, A., Srivastava, J., Kumar, V., A comparative study of anomaly detection schemes in network intrusion detection (2003) Proceedings of Third SIAM Conference on Data Mining, , San Francisco; Weiss, G.M., Mining with rarity: A unifying framework (2004) Sigkdd Explorations, 6 (1), pp. 7-19; Lewis, D.D., Gale, W.A., A sequential algorithm for training text classifiers (1994) Proceedings of International ACM Conference on Research and Development in Information Retrieval, pp. 3-12; Visa, S., Ralescu, A., Learning imbalanced and overlapping classes using fuzzy sets (2003) Workshop on Learning from Imbalanced Datasets II, , ICML, Washington DC; Sousa, A.V., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) LNCS, 3212. , Springer; Sousa, A.V., Mendonça, A.M., Campilho, A., Aguiar, R., Miranda, C.S., Feature extraction for classification of thin-layer chromatography images (2005) LNCS, 3656. , Springer; Japkowicz, N., Learning from imbalanced data sets: A comparison of various strategies (2000) Proceedings of Learning from Imbalanced Data, pp. 10-15; Kubat, M., Holte, R., Matwin, S., Machine learning for the detection of oil spills in satellite radar images (1998) Machine Learning, 30, pp. 195-215; Ha, T., Bunke, H., Off-Line, handwritten numeral recognition by perturbation method (1997) Pattern Analysis and Machine Intelligence, 19 (5), pp. 535-539; Lee, S., Noisy replication in skewed binary classification (2000) Computational Statistics & Data Analysis; Heijden, F., Robert, P.W.D., Ridder, D., Tax, D.M.J., (2004) Classification, Parameter Estimation and State Estimation, , Wiley; Demant, C., Streicher-Abel, B., Waszkewitz, P., (1999) Industrial Image Processing, , Springer-Verlag; Chawla, N.V., Bowyer, K., Hall, L., Kegelmeyer, W., SMOTE: Synthetic minority over-sampling technique (2002) Jounal of Artificial Intelligence Research, 16, pp. 321-357
Keywords: Chromatographic analysis; Class imbalanced problem; Classification (of information); Hierarchical systems; Lysosomal Storage Disorders (LSD); Medical imaging; Multiclassifier system; Problem solving; Thin-Layer Chromatography (TLC) images

Cultivation of human embryonic stem cells without the embryoid body step enhances osteogenesis in vitro - Karp, J.M.; Ferreira, L.S.; Khademhosseini, A.; Kwon, A.H.; Yeh, J.; Langer, R.S. (Stem CellsStem Cells, 2006)
Osteogenic cultures of embryonic stem cells (ESCs) are predominately derived from three-dimensional cell spheroids called embryoid bodies (EBs). An alternative method that has been attempted and merits further attention avoids EBs through the immediate separation of ESC colonies into single cells. However, this method has not been well characterized and the effect of omitting the EB step is unknown. Herein, we report that culturing human embryonic stem cells (hESCs) without the EB stage leads to a sevenfold greater number of osteogenic cells and to spontaneous bone nodule formation after 10-12 days. In contrast, when hESCs were differentiated as EBs for 5 days followed by plating of single cells, bone nodules formed after 4 weeks only in the presence of dexamethasone. Furthermore, regardless of the inclusion of EBs, bone matrix formed, including cement line matrix and mineralized collagen, which displayed apatitic mineral (PO 4) with calcium-to-phosphorous ratios similar to those of hydroxyapatite and human bone. Together these results demonstrate that culturing hESCs without an EB step can be used to derive large quantities of functional osteogenic cells for bone tissue engineering. ©AlphaMed Press.
Cited By (since 1996): 80Export Date: 21 November 2012Source: ScopusCODEN: STCEEdoi: 10.1634/stemcells.2005-0383Language of Original Document: EnglishCorrespondence Address: Langer, R.S.; Massachusetts Institute of Technology, 77 Massachusetts Ave., Cambridge, MA 02139-4307, United States; email: rlanger@mit.eduChemicals/CAS: apatite, 64476-38-6; calcium, 7440-70-2; collagen, 9007-34-5; dexamethasone, 50-02-2; hydroxyapatite, 1306-06-5, 51198-94-8; phosphorus, 7723-14-0; alkaline phosphatase, 9001-78-9; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; osteocalcin, 136461-80-8; Alkaline Phosphatase, 3.1.3.1; Calcium Phosphates; Collagen, 9007-34-5; Osteocalcin, 104982-03-8; calcium phosphate, 10103-46-5References: Langer, R., Vacanti, J.P., Tissue engineering (1993) Science, 260, pp. 920-926;Alsberg, E., Anderson, K.W., Albeiruti, A., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Bhatia, M., Derivation of the hematopoietic stem cell compartment from human embryonic stem cell lines (2005) Ann N Y Acad Sci, 1044, pp. 24-28; Thomson, J.A., Itskovitz-Eldor, J., Shapiro, S.S., Embryonic stem cell lines derived from human blastocysts (1998) Science, 282, pp. 1145-1147. , erratum in Science 1998 282:1827; Perlingeiro, R.C., Kyba, M., Daley, G.Q., Clonal analysis of differentiating embryonic stem cells reveals a hematopoietic progenitor with primitive erythroid and adult lymphoid-myeloid potential (2001) Development, 128, pp. 4597-4604; Zur Nieden, N.I., Kempka, G., Ahr, H.J., In vitro differentiation of embryonic stem cells into mineralized osteoblasts (2003) Differentiation, 71, pp. 18-27; Bourne, S., Polak, J.M., Hughes, S.P., Osteogenic differentiation of mouse embryonic stem cells: Differential gene expression analysis by cDNA microarray and purification of osteoblasts by cadherin-11 magnetically activated cell sorting (2004) Tissue Eng, 10, pp. 796-806; Buttery, L.D., Bourne, S., Xynos, J.D., Differentiation of osteoblasts and in vitro bone formation from murine embryonic stem cells (2001) Tissue Eng, 7, pp. 89-99; Shimko, D.A., Burks, C.A., Dee, K.C., Comparison of in vitro mineralization by murine embryonic and adult stem cells cultured in an osteogenic medium (2004) Tissue Eng, 10, pp. 1386-1398; Bronson, S.K., Bone nodule formation via in vitro differentiation of murine embryonic stem cells (2003) Methods Enzymol, 365, pp. 241-251; Sottile, V., Thomson, A., McWhir, J., In vitro osteogenic differentiation of human ES cells (2003) Cloning Stem Cells, 5, pp. 149-155; Bielby, R.C., Boccaccini, A.R., Polak, J.M., In vitro differentiation and in vivo mineralization of osteogenic cells derived from human embryonic stem cells (2004) Tissue Eng, 10, pp. 1518-1525; Cao, T., Heng, B.C., Ye, C.P., Osteogenic differentiation within intact human embryoid bodies result in a marked increase in osteocalcin secretion after 12 days of in vitro culture, and formation of morphologically distinct nodule-like structures (2005) Tissue Cell, 37, pp. 325-334; Ginis, I., Luo, Y., Miura, T., Differences between human and mouse embryonic stem cells (2004) Dev Biol, 269, pp. 360-380; Itskovitz-Eldor, J., Schuldiner, M., Karsenti, D., Differentiation of human embryonic stem cells into embryoid bodies compromising the three embryonic germ layers (2000) Mol Med, 6, pp. 88-95; Keller, G.M., In vitro differentiation of embryonic stem cells (1995) Curr Opin Cell Biol, 7, pp. 862-869; Yamada, T., Yoshikawa, M., Kanda, S., In vitro differentiation of embryonic stem cells into hepatocyte-like cells identified by cellular uptake of indocyanine green (2002) Stem Cells, 20, pp. 146-154; Aubin, J.E., Osteoprogenitor cell frequency in rat bone marrow stromal populations: Role for heterotypic cell-cell interactions in osteoblast differentiation (1999) J Cell Biochem, 72, pp. 396-410; Sarugaser, R., Lickorish, D., Baksh, D., Human umbilical cord perivascular (HUCPV) cells: A source of mesenchymal progenitors (2005) Stem Cells, 23, pp. 220-229; Komori, T., Yagi, H., Nomura, S., Targeted disruption of Cbfa1 results in a complete lack of bone formation owing to maturational arrest of osteoblasts (1997) Cell, 89, pp. 755-764; Bonewald, L.F., Harris, S.E., Rosser, J., Von Kossa staining alone is not sufficient to confirm that mineralization in vitro represents bone formation (2003) Calcif Tissue Int, 72, pp. 537-547; Amit, M., Carpenter, M.K., Inokuma, M.S., Clonally derived human embryonic stem cell lines maintain pluripotency and proliferative potential for prolonged periods of culture (2000) Dev Biol, 227, pp. 271-278; Karp, J.M., Shoichet, M.S., Davies, J.E., Bone formation on two-dimensional poly(DL-lactide-co-glycolide) (PLGA) films and three-dimensional PLGA tissue engineering scaffolds in vitro (2003) J Biomed Mater Res, 64 A, pp. 388-396; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Davies, J.E., In vitro modeling of the bone/implant interface (1996) Anat Rec, 245, pp. 426-445; Slizova, D., Krs, O., Pospisilova, B., Alternative method of rapid drying vascular specimens for scanning electron microscopy (2003) J Endovasc Ther, 10, pp. 285-287; Purpura, K.A., Aubin, J.E., Zandstra, P.W., Two-color image analysis discriminates between mineralized and unmineralized bone nodules in vitro (2003) Biotechniques, 34, pp. 1188-1192. , 1194, 1196 passim; Purpura, K.A., Aubin, J.E., Zandstra, P.W., Sustained in vitro expansion of bone progenitors is cell density dependent (2004) Stem Cells, 22, pp. 39-50; Klimanskaya, I., Chung, Y., Meisner, L., Human embryonic stem cells derived without feeder cells (2005) Lancet, 365, pp. 1636-1641; Draper, J.S., Pigott, C., Thomson, J.A., Surface antigens of human embryonic stem cells: Changes upon differentiation in culture (2002) J Anat, 200, pp. 249-258; Aubin, J.E., Liu, F., Malaval, L., Osteoblast and chondroblast differentiation (1995) Bone, 17, pp. 77S-83S; Aubin, J.E., Bone stem cells (1998) J Cell Biochem Suppl, 30-31, pp. 73-82; Schmitt, B., Ringe, J., Haupl, T., BMP2 initiates chondrogenic lineage development of adult human mesenchymal stem cells in high-density culture (2003) Differentiation, 71, pp. 567-577; Lian, J.B., McKee, M.D., Todd, A.M., Induction of bone-related proteins, osteocalcin and osteopontin, and their matrix ultrastructural localization with development of chondrocyte hypertrophy in vitro (1993) J Cell Biochem, 52, pp. 206-219; Wei, C.L., Miura, T., Robson, P., Transcriptome profiling of human and murine ESCs identifies divergent paths required to maintain the stem cell state (2005) Stem Cells, 23, pp. 166-185; Heng, B.C., Cao, T., Stanton, L.W., Strategies for directing the differentiation of stem cells into the osteogenic lineage in vitro (2004) J Bone Miner Res, 19, pp. 1379-1394
Keywords: alkaline phosphatase; Apatite; article; bone development; bone growth; bone matrix; bone mineralization; Bone tissue engineering; Calcium; calcium phosphate; Calcium phosphates; Cell Culture Techniques; cell differentiation; cell separation; Collagen; collagen synthesis; culture technique; cytology; dexamethasone; embryo; embryo culture; Embryoid bodies; embryonic stem cell; extracellular matrix; human; human cell; human embryo; Human embryonic stem cells; Humans; hydroxyapatite; in vitro study; Matrix characterization; metabolism; methodology; ossification; osteocalcin; Osteogenesis; Osteogenic cell frequency; phosphorus; spheroid cell; Tissue engineering; totipotent stem cell; Totipotent Stem Cells

Differentiation of mononuclear precursors into osteoclasts on the surface of Si-substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Spence, G.; McFarlane, I.; Lopes, M.A.; Best, S.M.; Santos, J.D.; Rushton, N.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
In healthy bone, resorption and synthesis are in perfect coordination. In previous studies we demonstrated that the incorporation of silicon into the hydroxyapatite (HA) lattice enhances the proliferation and differentiation of human osteoblasts. Therefore, the aim of this study was to demonstrate the effect of silicon-substituted HA (0.8 and 1.5 wt % Si-HA) on the differentiation of mononuclear cells into osteoclasts, using two different starting cultures, peripheral blood mononuclear cells (PBMC) and monocytes expressing the CD14 antigen (CD14 +). Through this study, it was possible to demonstrate that Si-HA allows the differentiation of mononuclear cells into mature osteoclasts, independent of the starting culture, PBMC or CD14 +. Most of the cells on the surface of the materials expressed osteoclastic markers: actin rings, several nuclei, positivity for tartrate-resistant acid phosphatase (TRAP), and vitronectin receptor. In the presence of osteoclasts, a higher release of calcium and phosphate into the medium from the 1.5 wt % Si-HA substrate was detected when compared to the HA substrate; therefore, these results indicate higher osteoclastic resorptive activity on the 1.5 wt % Si-HA surface. Si-HA can be resorbed by cellular mechanisms and have a stimulatory effect on osteoclasts, although the underlying mechanism is still poorly understood. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30726PubMed ID: 16739170Language of Original Document: EnglishCorrespondence Address: Brooks, R.A.; Orthopaedic Research Unit, Box 180, Addenbrooke's Hospital, Hills Road, Cambridge CB2 2QQ, United Kingdom; email: rb10003@cam.ac.ukChemicals/CAS: calcium, 7440-70-2; hydroxyapatite, 1306-06-5, 51198-94-8; phosphate, 14066-19-4, 14265-44-2; silicon, 7440-21-3; Antigens, CD14; Durapatite, 1306-06-5; Silicon, 7440-21-3References: Schilling, A., Linhart, W., Filke, S., Gebauer, M., Schinke, T., Rueger, J., Amling, M., Resorbability of bone substitute biomaterials by human osteoclasts (2004) Biomaterials, 25, pp. 3963-3972;Miller, P., Baram, D., Bilezkian, J., Greenspan, S., Lindsay, R., Riggs, B., Watts, N., Practical clinical application of biochemical markers of bone turnover: Consensus of an expert panel (1999) J Clin Densitom, 2, pp. 323-342; Flanagan, A., Massey, H., Wilson, C., Vellodi, A., Horton, M.A., Steward, C., Macrophage colony-stimulating factor and receptor activator NF-κ B ligand fail to rescue osteoclast-poor human malignant infantile osteopetrosis in vitro (2002) Bone, 30, pp. 85-90; Boyle, W., Simonet, W., Lacey, D.L., Osteoclast differentiation and activation (2003) Nature, 423, pp. 337-342; Susa, M., Luong-Nguyen, N.H., Cappellen, D., Zamurovic, N., Gamse, R., Human primary osteoclasts in vitro generation and applications as a pharmacological and clinical assay (2004) J Transl Med, 2, p. 6; Anderson, D., Maraskovsky, E., Bilingsley, W., Dougal, W., Tometsko, M., Roux, E., Teepe, M., Gilbert, L., A homologue of the TNF receptor and its ligand enhance T-cell growth and dendritic-cell function (1997) Nature, 390, pp. 175-179; Matsuzaki, K., Udagawa, N., Takahashi, N., Yamaguchi, K., Yasuda, H., Shima, N., Morinaga, T., Suda, T., Osteoclast differentiation factor (ODF) induces osteoclast-like cell formation in human peripheral blood mononuclear cell cultures (1998) Biochem Biophys Res Commun, 246, pp. 199-204; Quinn, J., Elliot, J., Gillespie, M., Martin, T., A combination of Osteoclast differentiation factor and macrophage-colony stimulating factor is sufficient for both human and mouse osteoclast formation in vitro (1998) Endocrinology, 139, pp. 4424-4427; Massey, H., Flanagan, A., Human osteoclasts derive from CD14-positive monocytes (1999) Br J Haematol, 106, pp. 167-170; Horton, M., The α vβ 3 integrin "vitronectin receptor" (1997) Int J Biochem Cell Biol, 29, pp. 721-725; Doi, Y., Shibutani, T., Moriwaki, Y., Kajimoto, T., Iwayama, Y., Sintered carbonate apatites as bioresorbable bone substitutes (1998) J Biomed Mater Res, 39, pp. 603-610; Langstaff, S., Sayer, M., Smith, T., Pugh, S., Resorbable bioceramics based on stabilized calcium phosphates. Part II: Evaluation of biological response (2001) Biomaterials, 22, pp. 135-150; Patel, N., Best, S.M., Gibson, I.R., Hing, K.A., Damien, E., Revell, P.A., A comparative study on the in vivo behaviour of hydroxyapatite and silicon-substituted hydroxyapatite granules (2002) J Mater Sci Mater Med, 13, pp. 1199-1206; Botelho, C.M., Brooks, R.A., Lopes, M.A., Santos, J.D., Best, S.M., Rushton, N., Bonfield, W., Biological and physical-chemical characterization of phase pure hydroxyapatite and silicon-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254-256, pp. 845-849; Gibson, I.R., Hung, J., Best, S.M., Bonfield, W., Enhanced in vitro cell activity and surface apatite layer formation on novel silicon-substituted hydroxyapatites (1999) Bioceramics, 12, pp. 191-194. , Ohgushi H, Hastings GW, Yoshikawa T, editors. Nara, Japan: World Scientific Publishing; Jha, L.J., Best, S.M., Santos, J.D., Gibson, I.R., Bonfield, W., Silicon-substituted apatites and process for the preparation thereof. Worldwide Pat PCT/GB97/02325, 1999Gibson, I., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44 B, pp. 422-428; Botelho, C.M., Lopes, M.A., Gibson, I.R., Best, S.M., Santos, J.D., Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy (XPS) (2002) J Mater Sci: Mater Med, 13, pp. 1123-1127; Winchester, R.J., Ross, G., Methods for enumerating lymphocyte populations (1976) Manual of Clinical Immunology, pp. 64-76. , Rose NR, Friedman H, editors. Washington, DC: American Society for Microbiology; Burstone, M.S., Histochemical demonstration of acid phosphatases with naphthol AS-phosphate (1958) J Natl Cancer Inst, 21, pp. 423-539; Monchau, F., Lefevre, A., Descamps, M., Belquin-Myrdyez, A., Laffargue, P., Hildebrand, H.F., In vitro studies of human and rat osteoclast activity on hydroxyapatite, β-tricalcium phosphate, calcium carbonate (2002) Biomol Eng, 19, pp. 143-152; Chambers, T.J., The regulation of osteoclastic development and function (1988) Ciba Foundation Symposium, 136, pp. 92-107; Lakkakorpi, P., Tuukkanen, J., Hentunen, J., Jarvelin, K., Vaananen, K., Organization of osteoclast microfilaments during the attachment to bone surface in vitro (1989) J Bone Miner Res, 4, pp. 817-825; Nesbitt, S., Horton, M.A., Trafficking of matrix collagens through bone-resorbing osteoclasts (1997) Science, 276, pp. 266-269; Salo, J., Lehenkari, P., Removal of osteoclast bone resorption products by transcytosis (1997) Science, 276, pp. 270-273; Vaananen, K., Horton, M.A., The osteoclast clear zone is a specialized cell extracellular matrix adhesion structure (1995) J Cell Sci, 108, pp. 2729-2732; Kong, Y.Y., Feige, U., Sarosi, I., Bolon, B., Tafuri, A., Morony, S., Cappareli, C., Boyle, W.J., OPGL is a key regulator of osteoclastogenesis, lymphocyte development and lymph-node organogenesis (1999) Nature, 402, pp. 304-309; Wittrant, Y., Thepleyre, S., Couillaud, S., Dunstan, C., Heymann, D., Rédini, F., Relevance of an in vitro osteoclastogenesis system to study receptor activator of NF-κ B ligand and osteoprotegerin biological activities (2004) Exp Cell Res, 93, pp. 292-301; Heymann, D., gp130 cytokine family and bone cells (2000) Cytokine, 12, pp. 1455-1468; Heymann, D., Gouin, F., Passuti, N., Daculsi, G., Cytokines, growth factors and osteoclasts (1998) Cytokine, 10, pp. 155-168; Burgess, T., Qian, Y., Kaufman, S., Ring, B., Van, G., Capparelli, C., The ligand for osteoprotegerin (OPGL) directly activates mature osteoclasts (1999) J Cell Biol, 145, pp. 527-538; Teitelbaum, S., Bone resorption by osteoclasts (2000) Science, 289, pp. 1504-1508; Udagawa, N., Takahashi, N., Jimi, E., Matsuzaki, K., Tsurukai, T., Itoh, K., Nakagawa, N., Goto, M., Osteoblasts/stromal cells stimulate osteoclast activation through expression of osteoclast differentiation factor/RANKL but not macrophage colony-stimulating factor (1999) Bone, 25, pp. 517-523; Zhang, Y.M., Cai, Y.R., Monchau, F., Lefevre, A., Zhao, Y.M., Hildebrand, H.F., Biodegradation of synthetic bioglass with different crystallinity in vitro (2004) Seventh World Biomaterials Congress, p. 1904. , Sydney; Gomi, K., Lowenberg, B., Shapiro, G., Davies, J.E., Resorption of sintered synthetic hydroxyapatite by osteoclasts in vitro (1993) Biomaterials, 2, pp. 91-96; De Bruijin, J.D., Bovel, Y.P., Davies, J.E., Van Blitterswijik, C.A., Osteoclastic resorption of calcium phosphate is potentiated in postosteogenic culture conditions (1994) J Biomed Mater Res, 28, pp. 105-112; Botelho, C.M., Brooks, R.A., Kawai, T., Ogata, S., Ohtsuki, C., Best, S.M., Lopes, M.A., Bonfield, W., In vitro analysis of protein adhesion to phase pure hydroxyapatite and silicon-substituted hydroxyapatite (2005) Key Eng Mat, 284-286, pp. 461-464
Keywords: acid phosphatase tartrate resistant isoenzyme; actin; Antigens, CD14; article; Biomarkers; Calcium; CD14 antigen; cell differentiation; Cells; controlled study; Differentiation; Durapatite; human; human cell; hydroxyapatite; Microscopy, Fluorescence; monocyte; Monocytes; Monocytes CD14 positive; Osteoblasts; osteoclast; Osteoclasts; osteolysis; peripheral blood mononuclear cell; Peripheral blood mononuclear cells; phosphate; Silicon; Silicon-substituted hydroxyapatite; Sorption; Substitution reactions; Substrates; surface property; Synthesis (chemical); vitronectin receptor

Effect of surface treatments on anodic oxide film growth and electrochemical properties of tantalum used for biomedical applications - Silva, R.A.; Silva, I.P.; Rondot, B. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2006)
Self-expandable nitinol (nickel-titanium) alloys and 316L stainless steel are the most commonly used materials in the production of coronary stents. However, tantalum (Ta) has already been used to make stents for endovascular surgery and may constitute an alternative to other materials because of its better electrochemical performance, namely its higher corrosion resistance, as well as its radio-opacity. The characterization of wet polished, chemically polished, wet polished anodized, and chemically polished anodized Ta electrodes has been performed in a 0.15 M NaCl solution (simulated body fluid) using U corr=f(t) measurements, anodic polarizations, capacity measurements, anodic oxidations, and atomic force microscopy (AFM) imaging. Anodic polarization curves have shown that the abnormal current density peak with a maximum value around 1.65 V (critical applied potential, U c) disappeared for the anodized electrodes indicating a probable relationship between the surface states and the film growth. These results are confirmed by capacity measurements. The behavior of wet polished and chemically polished electrodes during anodic oxidations seemingly indicated that for these particular treatments the film growth is different. The AFM images and roughness measurements have shown that chemical polishing produced smoother electrodes, a fact probably related to the differences in film growth. © 2006 Sage Publications.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBAPEdoi: 10.1177/0885328206056378Language of Original Document: EnglishCorrespondence Address: Silva, R.A.; Instituto Superior de Engenharia do Porto, ISEP-CIEA, Rua Dr. A.B. de Almeida, 431, 4200-072 Porto, Portugal; email: ras@isep.ipp.ptChemicals/CAS: oxide, 16833-27-5; tantalum, 7440-25-7; Biocompatible Materials; Membranes, Artificial; Oxides; Tantalum, 7440-25-7References: Goy, J.J., Eeckhout, E., Stauffer, J.C., Vogt, P., Kappenberger, L., Emergency Endoluminal Stenting for Abrupt Vessel Closure following Coronary Angioplasty: A Randomised Comparison of the Wiktor and Palmaz-Schatz Stents (1995) Catheter. Cardiov. Diag., 34 (2), pp. 128-132;Hamasaki, N., Nosaka, H., Kimura, T., Nakagawa, Y., Yokoi, H., Nobuyioshi, M., Initial Experience with the Cordis Stent: Analysis of Serial Angiographic Follow-up (1995) Catheter. Cardiov. Diag., 42 (2), pp. 166-172; Hamm, C.W., Beythien, C., Sievert, H., Langer, A., Multicenter Evaluation of the Strecker Tantalum Stent for Acute Coronary Occlusion after Angioplasty (1995) Amer. Heart J., 129 (3), pp. 423-429; Strecker, E.-P.K., Boos, I.B.L., Göttman, D.V.S., Haase, W., Popliteal Artery Stenting Using Flexible Tantalum Stents (2001) Cardiovasc. Intervent. Radiol., 24 (3), pp. 168-175; Rieger, J., Hautmann, H., Linsenmaier, U., Weber, C., Treitl, M., Huber, R.M., Pfeifer, K.-J., Treatment of Benign and Malignant Tracheobronchial Obstruction with Metal Wire Stents: Experience with a Balloon-expandable and a Self Expandable Stent Type (2004) Cardiovasc. Intervent. Radiol., 27 (4), pp. 339-343; Bertrand, O.F., Sipehia, R., Mongrain, R., Rodes, J., Tardif, J.C., Bilodeau, L., Cote, G., Bourassa, M.G., Biocompatibility Aspect of New Stent Technology (1998) J. Am. Coll. Cardiol., 32 (3), pp. 562-571; Shih, C.-C., Lin, S.-J., Chung, K.-H., Chen, Y.-L., Su, Y.-Y., Increased Corrosion Resistance of Stent Materials by Converting Current Surface Film of Polycrystalline Oxide into Amorphous Oxide (2000) J. Biomed. Mater. Res., 52 (2), pp. 323-332; Thierry, B., Tabrizian, M., Trepanier, C., Savadogo, O., Yahia, L.H., Effect of Surface Treatment and Sterilization Processes on the Corrosion Behavior of NiTi Shape Memory Alloy (2000) J. Biomed. Mater. Res., 51 (4), pp. 685-693; Macionczyc, F., Gerold, B., Thull, R., Repassivating Tantalum/Tantalum Oxide Surface Modification on Stainless Steel (2001) Surface and Coatings Technology, 142-144, pp. 1085-1087; Starovesky, D., Gotman, I., Corrosion of Titanium Nitride Coated Ni-Ti Shape Memory Surgical Implant (2001) Biomaterials, 22 (13), pp. 1853-1859; Chen, J.Y., Leng, Y.X., Tian, X.B., Wang, L.P., Huang, N., Chu, P.K., Yang, P., Antithrombogenic Investigation of Surface Energy and Optical Bandgap and Hemocompatibility Mechanism of Ti(Ta(+5))O 2 (2002) Biomaterials, 23 (12), pp. 2545-2552; Tan, L., Crone, W.C., Sridharan, K., Fretting Study of Surface Modified Ni-Ti Shape Memory Alloy (2002) J. Mater. Sci. Mater. Med., 13 (5), pp. 501-508; Cissé, O., Savadogo, O., Wu, M., Yahia, L.H., Effect of Surface Treatment of NiTi Alloy on its Corrosion Behavior in Hank's Solution (2002) J. Biomed. Mater. Res., 61 (3), pp. 339-345; Schabalovskaya, S., Rondelli, G., Anderegg, J., Simpson, B., Budko, S., Effect of Chemical Etching and Aging in Boiling Water on the Corrosion Resistance of Nitinol Wires with Black Oxide Resulting from Manufacturing Process (2003) J. Biomed. Mater. Res., 66 B (1), pp. 331-340; Shih, C.-C., Shih, C.-M., Su, Y.-Y., Lin, S.-J., Impact on the Thrombogenicity of Surface Oxide Properties of 316L Stainless Steel for Biomedical Applications (2003) J. Biomed. Mater. Res., 67 A, pp. 1320-1328; Cheng, Y., Cai, W., Li, H.T., Zheng, Y.F., Zhao, L.C., Surface Characteristics and Corrosion Resistance Properties of TiNi Shape Memory Alloy Coated with Tantalum (2004) Surface and Coatings Technology, 186 (3), pp. 346-352; Silva, R.A., Marques, M.A., Silveira, A., Walls, M., Rondot, B., Guidoin, R., (1998) Proceedings of the 14th European Conference on Biomaterials, pp. 37-37. , (eds) In: Dutch Society for Biomaterials, September, The Hague; Pippen, C.M.J.M., Plenk Jr., H., Ebel, M.F., Svagera, R., Verenisch, J., Characterization of Microblasted and Reactive Ion Etched Surfaces on the Commercially Pure Metals Niobium, Tantalum and Titanium (1997) J. Mater. Sci.: Mater. in Med., 8 (12), pp. 781-784; Park, J.B., (1994) Biomaterials Science and Engineering, pp. 217-217. , (ed.) Plenum Press, New York; Jonhson, P.F., Bernstein, J.J., Hunter, G., Dawson, W.W., Hench, L.L., An in vitro and in vivo Analysis of Anodised Tantalum Capacitive Electrodes: Corrosion Response, Physiology, and Histology (1997) J. Biomed. Mater. Res., 11 (5), pp. 637-656; Black, J., Biological Performance of Tantalum (1994) Clin. Mater., 16 (3), pp. 167-173; Stackpool, G.J., Kay, A.B., Morton, P., Harvey, E.J., Tanzer, M., Bone, J.D., (1995) Proceedings of Combined Orthopaedic Research Societies Meeting, Orthopaedic, pp. 45-45. , (eds) In: Research Society Rider Dickerson Inc., Chicago; Silva, R.A., Walls, M., Rondot, B., Da Cunha Belo, M., Guidoin, R., Electrochemical and Microstructural Studies of Tantalum and its Oxide Films for Biomedical Applications in Endovascular Surgery (2002) J. Mater. Sci.: Mater. Medicine, 13 (5), pp. 495-500; Lohrengel, M.M., Formation of Ionic Space Charge Layers in Oxide Films on Valve Metals (1994) Electrochim. Acta, 39 (8-9), pp. 1265-1271; Macagno, V.A., Schultze, J.W., The Growth and Properties of Thin Oxide Layers on Tantalum Electrodes (1984) J. Electroanal. Chem., 180 (1), pp. 157-170; Schultze, J.W., Macagno, V.A., Electron Transfer Reaction on Passive Tantalum Electrodes (1986) Electrochim. Acta, 31 (1), pp. 355-363; Kerrec, O., Devilliers, D., Groult, H., Chemla, M., Dielectric Properties of Anodic Oxide Films on Tantalum (1995) Electrochim. Acta, 40 (6), pp. 719-724; Lewerenz, H.J., Anodic Oxide Films on Silicon (1992) Electrochim. Acta, 37 (10), pp. 847-851; Young, L., (1961) Anodic Oxide Films, , Academic Press, London; Seah, M.P., Holbourn, M.W., Ortega, C., Davies, J.A., An Intercomparison of Tantalum Pentoxide Reference Studies (1988) Nuclear Instruments and Methods in Physics Research, B30 (2), pp. 128-139
Keywords: AFM; Anodic films; Anodic oxide film growth; Anodic polarization; article; artificial membrane; Atomic force microscopy; Biocompatible Materials; biomaterial; Biomedical applications; Biomedical engineering; Chemical polishing; chemistry; Coronary stents; Corrosion resistance; Crystallization; Current density; electric conductivity; Electrochemical properties; electrochemistry; electrode; Electrodes; materials testing; Membranes, Artificial; methodology; oxidation reduction reaction; Oxidation-Reduction; oxide; Oxides; Polarization; Surface Properties; surface property; Surface treatment; Tantalum; Tantalum electrodes

Error entropy in classification problems: A univariate data analysis - Silva, L.M.; Felgueiras, C.S.; Alexandre, L.A.; Marques de Sá, J. (Neural ComputationNeural Comp., 2006)
Entropy-based cost functions are enjoying a growing attractiveness in unsupervised and supervised classification tasks. Better performances in terms both of error rate and speed of convergence have been reported. In this letter, we study the principle of error entropy minimization (EEM) from a theoretical point of view. We use Shannon's entropy and study univariate data splitting in two-class problems. In this setting, the error variable is a discrete random variable, leading to a not too complicated mathematical analysis of the error entropy. We start by showing that for uniformly distributed data, there is equivalence between the EEM split and the optimal classifier. In a more general setting, we prove the necessary conditions for this equivalence and show the existence of class configurations where the optimal classifier corresponds to maximum error entropy. The presented theoretical results provide practical guidelines that are illustrated with a set of experiments with both real and simulated data sets, where the effectiveness of EEM is compared with the usual mean square error minimization. © 2006 Massachusetts Institute of Technology.
Cited By (since 1996): 7Export Date: 21 November 2012Source: Scopusdoi: 10.1162/neco.2006.18.9.2036PubMed ID: 16846386Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; Institute de Engenharia Biomédica, Laboratório Sinal e Imagem Biomédica, 4200-465, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Devroye, L., Gyorfi, L., Lugosi, G., (1996) A Probabilistic Theory of Pattern Recognition, , Berlin: Springer-Verlag;Erdogmus, D., Principe, J., Comparison of entropy and mean square error criteria in adaptive system training using higher order statistics (2000) Proceedings of the Intl. Conf., on ICA and Signal Separation, pp. 75-80. , Helsinki, Finland; Erdogmus, D., Principe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Kapur, J., (1993) Maximum-entropy Models in Science and Engineering (Rev. Ed), , New York: Wiley; Kullback, S., (1959) Statistics and Information Theory, , New York: Wiley; Linsker, R., Self-organization in a perceptual network (1988) IEEE Computer, 21, pp. 105-117; Marques De Sa, J., (2001) Pattern Recognition: Concepts, Methods and Applications, , Berlin: Springer-Verlag; Newman, D., Hettich, S., Blake, C., Merz, C., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html, Irvine: University of California, Irvine, Department of Information and Computer Sciences; Parzen, E., On the estimation of a probability density function and the mode (1962) Annals of Mathematical Statistics, 33, pp. 1065-1076; Press, W., Teukolsky, S., Vetterling, W., Flannery, B., (1992) Numerical Recipes in C: The Art of Scientific Computing, , Cambridge: Cambridge University Press; Principe, J.C., Xu, D., Fisher, J., Information theoretic learning (2000) Unsupervised Adaptive Filtering, Vol. 1: Blind Source Separation, 1, pp. 265-319. , S. Haykin (Ed.), New York: Wiley; Santos, J., Alexandre, L., Marques De Sá, J., The error entropy minimization algorithm for neural network classification (2004) Int. Conf. on Recent Advances in Soft Computing, , Nottingham, U.K.: Nottingham Trent University; Santos, J., Marques De Sa, J., Alexandre, L., Sereno, F., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, & O. Ersoy (Eds.), New York: American Society of Mechanical Engineers; Shannon, C.E., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423; Silva, L., Marques De Sa, J., Alexandre, L., Neural network classification using Shannon's entropy (2005) European Symposium on Artificial Neural Networks, , Bruges, Belgium: d-side publications; Silverman, B., (1986) Density Estimation for Statistics and Data Analysis, , London: Chapman & Hall; Stoller, D., Univariate two-population distribution free discrimination (1954) Journal of the American Statistical Association, 49, pp. 770-777
Keywords: article; Classification; entropy; methodology; Models, Theoretical; normal distribution; theoretical model

Error entropy minimization for LSTM training - Alexandre, L.A.; Marques De Sá, J.P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
In this paper we present a new training algorithm for the Long Short-Term Memory (LSTM) recurrent neural network. This algorithm uses entropy instead of the usual mean squared error as the cost function for the weight update. More precisely we use the Error Entropy Minimization approach, were the entropy of the error is minimized after each symbol is present to the network. Our experiments show that this approach enables the convergence of the LSTM more frequently than with the traditional learning algorithm. This in turn relaxes the burden of parameter tuning since learning is achieved for a wider range of parameter values. The use of EEM also reduces, in some cases, the number of epochs needed for convergence. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68317Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; Department of Informatics, IT-Networks and Multimedia Group, University of Beira Interior, Covilhã, Portugal; email: lfbaa@di.ubi.ptReferences: Hochreiter, S., Schmidhuber, J., Long short-term memory (1997) Neural Computation, 9 (8), pp. 1735-1780;Gers, F., Schmidhuber, J., Cummins, F., Learning to forget: Continual prediction with LSTM (2000) Neural Computation, 12 (10), pp. 2451-2471; Gers, F., Schmidhuber, J., Recurrent nets that time and count (2000) Proc. IJCNN'2000, Int. Joint Conf. on Neural Networks, , Como, Italy; Pérez-Ortiz, J., Gers, F., Eck, D., Schmidhuber, J., Kalman filters improve LSTM network performance in problems unsolvable by traditional recurrent nets (2003) Neural Networks, 16 (2), pp. 241-250; Haykin, S., (1999) Neural Networks: A Comprehensive Foundation, 2nd Edition, , Prentice Hall; Erdogmus, D., Principe, J., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Trans. Signal Processing, 50 (7), pp. 1780-1786; Santos, J., Alexandre, L., Sereno, F., Marques De Sá, J., Optimization of the error entropy minimization algorithm for neural network classification (2004) ANNIE 2004, Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , St.Louis, USA, ASME Press Series; Santos, J., Alexandre, L., Marques De Sá, J., The error entropy minimization algorithm for neural network classification (2004) Proceedings of the 5th International Conference on Recent Advances in Soft Computing, pp. 92-97. , Lofti, A., ed.: Nottingham, United Kingdom; Silva, L., Marques De Sá, J., Alexandre, L., Neural network classification using Shannon's entropy (2005) 13th European Symposium on Artificial Neural Networks - ESANN 2005, pp. 217-222. , Bruges, Belgium
Keywords: Algorithms; Convergence of numerical methods; Cost function; entropy; Error Entropy Minimization; Errors; Long Short-Term Memory (LSTM); Neural networks; Optimization

Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers - Rodrigues, S.N.; Gonçalves, I.C.; Martins, M.C.L.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2006)
The effect of surface wettability on fibrinogen adsorption, platelet adhesion and platelet activation was investigated using self-assembled monolayers (SAMs) containing different ratios of longer chain methyl- and shorter chain hydroxyl-terminated alkanethiols (C15CH3 vs. C11OH) on gold. Protein adsorption studies were performed using radiolabeled human fibrinogen (HFG). Platelet adhesion and activation studies with and without pre-adsorbed fibrinogen, albumin and plasma were assessed using scanning electron microscopy (SEM) and a glutaraldehyde-induced fluorescence technique (GIFT). Results demonstrated a linear decrease of HFG adsorption with the increase of OH groups on the monolayer (increase of the hydrophilicity). Platelet adhesion and activation also decrease with increase of hydrophilicity of surface. Concerning SAMs pre-immersed in proteins, fibrinogen adsorption was related with high platelet adhesion and activation. The passivant effect of albumin on platelet adhesion and activation was only demonstrated on SAMs contained C11OH. When all the blood proteins are present (plasma) platelet adhesion was almost absent on SAMs with 65% and 100% C11OH. This could be explained by the higher albumin affinity of the SAMs with 65% C11OH and the lower total protein adsorption associated with SAMs with 100% C11OH. © 2006 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 70Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2006.06.010PubMed ID: 16842847Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: fibrinogen, 9001-32-5; glutaraldehyde, 111-30-8, 37245-61-7; gold, 7440-57-5; thiol derivative, 13940-21-1; Alkanes; Biocompatible Materials; Fibrinogen, 9001-32-5; hydroxide ion, 14280-30-9; Hydroxides; Sulfhydryl CompoundsReferences: Savage, B., Ruggeri, Z.M., Selective recognition of adhesive sites in surface-bound fibrinogen by glycoprotein-iib-iiia on nonactivated platelets (1991) J Biol Chem, 266 (17), pp. 11227-11233;Tsai, W.B., Grunkemeier, J.M., McFarland, C.D., Horbett, T.A., Platelet adhesion to polystyrene-based surfaces preadsorbed with plasmas selectively depleted in fibrinogen, fibronectin, vitronectin, or von Willebrand's factor (2002) J Biomed Mater Res, 60 (3), pp. 348-359; Kottkemarchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the invitro blood compatibility of dacron arterial prostheses (1989) Biomaterials, 10 (3), pp. 147-155; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27 (12), pp. 1463-1476; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13 (13), pp. 3404-3413; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption on 18-alkyl chains immobilized on hydroxyl-terminated self-assembled monolayers (2005) Biomaterials, 26 (18), pp. 3891-3899; Peters, T., (1996) All about albumin: biochemistry, genetics and medical applications, , Academic Press Inc., San Diego, CA; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolavers (2003) J Biomed Mater Res A, 67 A (1), pp. 158-171; Frank, R.D., Dresbach, H., Thelen, H., Sieberth, H.G., Glutaraldehyde induced fluorescence technique (GIFT): a new method for the imaging of platelet adhesion on biomaterials (2000) J Biomed Mater Res, 52 (2), pp. 374-381; Feng, L., Andrade, J.D., Protein adsorption on low-temperature isotropic carbon. 3. Isotherms, competitivity, desorption and exchange of human albumin and fibrinogen (1994) Biomaterials, 15 (5), pp. 323-333; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., Spontaneously organized molecular assemblies. 4. Structural characterization of normal-alkyl thiol monolayers on gold by optical ellipsometry, infrared-spectroscopy, and electrochemistry (1987) J Am Chem Soc, 109 (12), pp. 3559-3568; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120 (14), pp. 3464-3473; Goodman, S.L., Sheep, pig, and human platelet-material interactions with model cardiovascular biomaterials (1999) J Biomed Mater Res, 45 (3), pp. 240-250; Slack, S.M., Horbett, T.A., Changes in fibrinogen adsorbed to segmented polyurethanes and hydroxyethylmethacrylate-ethylmethacrylate copolymers (1992) J Biomed Mater Res, 26 (12), pp. 1633-1649; Andrade, J.D., Hlady, V., Protein adsorption and materials biocompatibility-a tutorial review and suggested hypotheses (1986) Adv Polym Sci, 79, pp. 1-63; Roach, P., Farrar, D., Perry, C.C., Interpretation of protein adsorption: surface-induced conformational changes (2005) J Am Chem Soc, 127 (22), pp. 8168-8173; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interf Sci, 185 (1), pp. 94-103; Lin, Y., Wang, J., Wan, L.J., Fang, X.H., Study of fibrinogen adsorption on self-assembled monolayers on Au (1 1 1) by atomic force microscopy (2005) Ultramicroscopy, 105 (1-4), pp. 129-136; Norde, W., Favier, J.P., Structure of adsorbed and desorbed proteins (1992) Colloid Surf, 64 (1), pp. 87-93; Alfonsi-Hourdin, S., Longchamp, S., Gallet, O., Nigretto, J.M., Electrochemical processing of fibrinogen modified-graphite surfaces: effect on plasmin generation from adsorbed plasminogen (2006) Biomaterials, 27 (1), pp. 52-60; Tsai, W.B., Shi, Q., Grunkemeier, J.M., McFarland, C., Horbett, T.A., Platelet adhesion to radiofrequency glow-discharge-deposited fluorocarbon polymers preadsorbed with selectively depleted plasmas show the primary role of fibrinogen (2004) J Biomater Sci-Polym E, 15 (7), pp. 817-840; Stryer, L., (1998) Biochemistry. 4th ed., , WH Freeman, New York; Doolittle, R.F., Watt, K.W.K., Cottrell, B.A., Strong, D.D., Riley, M., Amino-acid sequence of the alpha-chain of human-fibrinogen (1979) Nature, 280 (5722), pp. 464-468; Kloczewiak, M., Timmons, S., Lukas, T.J., Hawiger, J., Platelet receptor recognition site on human-fibrinogen-synthesis and structure-function relationship of peptides corresponding to the carboxy-terminal segment of the gamma-chain (1984) Biochemistry, 23 (8), pp. 1767-1774; Tsai, W.B., Grunkemeier, J.M., Horbett, T.A., Variations in the ability of adsorbed fibrinogen to mediate platelet adhesion to polystyrene-based materials: a multivariate statistical analysis of antibody binding to the platelet binding sites of fibrinogen (2003) J Biomed Mater Res A, 67 A (4), pp. 1255-1268; Salsmann, A., Schaffner-Reckinger, E., Kabile, F., Plancon, S., Kieffer, N., A new functional role of the fibrinogen RGD motif as the molecular switch that selectively triggers integrin alpha IIb beta 3-dependent RhoA activation during cell spreading (2005) J Biol Chem, 280 (39), pp. 33610-33619; Lin, J.C., Chuang, W.H., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51 (3), pp. 413-423; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Kasori, Y., Shiroya, T., Blood compatible aspects of poly(2-methoxyethylacrylate) (PMEA)-relationship between protein adsorption and platelet adhesion on PMEA surface (2000) Biomaterials, 21 (14), pp. 1471-1481; Barbucci, R., Lamponi, S., Magnani, A., Fibrinogen conformation and platelet reactivity in relation to material-blood interaction: effect of stress hormones (2003) Biomacromolecules, 4 (6), pp. 1506-1513; Hylton, D.M., Shalaby, S.W., Latour, R.A., Direct correlation between adsorption-induced changes in protein structure and platelet adhesion (2005) J Biomed Mater Res A, 73 A (3), pp. 349-358; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomat Sci-Polym E, 4 (6), pp. 591-599
Keywords: Adsorption; Albumin; alkane derivative; Alkanes; article; binding affinity; Biocompatible Materials; Blood Platelets; Cells, Cultured; Chemical reactions; controlled study; Crystallization; fibrinogen; Fluorescence; fluorescence analysis; glutaraldehyde; gold; human; human cell; Humans; hydrophilicity; Hydroxides; hydroxyl group; materials testing; methyl group; Methylation; monolayer culture; Monolayers; normal human; Organic compounds; plasma; Plasma protein; Platelet activation; Platelet adhesion; Platelet Adhesiveness; priority journal; Protein adsorption; protein binding; Proteins; Radiolabeled human fibrinogen (HFG); Scanning electron microscopy; Self assembled; SEM; Sulfhydryl Compounds; surface property; thiol derivative; thrombocyte adhesion; wettability

Functionalization of chitosan membranes through phosphorylation: Atomic force microscopy, wettability, and cytotoxicity studies - Amaral, I.F.; Granja, P.L.; Melo, L.V.; Saramago, B.; Barbosa, M.A. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 2006)
Grafting negatively charged groups such as phosphates is a well-known strategy for inducing the deposition of apatite-like layers under simulated physiological conditions. In this investigation, chitosan was phosphorylated in an attempt to enhance its osteoconduction. Chitosan membranes were phosphorylated at 30°C with the H 3PO 4/ Et 3PO 4/P 2O 5/butanol reaction system for periods up to 48 h. This method is an alternative to the phosphoric acid/ urea/dimethylformamide phosphorylation method, which involves the use of much higher temperatures. In this study, the effects of the phosphorylation reaction time on the surface morphology and surface free energy of phosphorylated membranes were investigated with atomic force microscopy and static-contact-angle measurements, respectively. In addition, the modified membranes were evaluated with respect to their cytotoxiciry toward bone cells through the incubation of human osteoblastic cells with extracts of the materials for two different periods: 24 and 120 h. The results revealed a reduction of the average surface roughness at the nanometer scale with increasing phosphorylation reaction time. Wettability studies showed an increase in the polar component of the surface free energy with increasing reaction time as a result of the increase in the phosphate surface concentration. Cytotoxicity studies revealed no cytotoxic effect of phosphorylated membranes on osteoblastic cells, regardless of the incubation period. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JAPNAdoi: 10.1002/app.23737Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; Laboratório de Biomateriais, Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptReferences: Tomihata, K., Ikada, Y., (1997) Biomaterials, 18, p. 567;VandeVord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., (2002) J Biomed Mater Res, 59, p. 585; Khor, E.C., (2001) Fulfilling a Biomaterials Promise, , Elsevier: Oxford; Peluso, G., Petillo, O., Ranieri, M., Santin, M., Ambrosio, L., Calabro, D., Avallone, B., Balsamo, G., (1994) Biomaterials, 15, p. 1215; Muzzarelli, R.A.A., (1997) CeUul Mol Life Sci, 53, p. 131; Ishihara, M., Nakanishi, K., Ono, K., Sato, M., Kikuchi, M., Saito, Y., Yura, H., Kurita, A., (2002) Biomaterials, 23, p. 833; Muzzarelli, R.A.A., Zucchini, C., Ilari, P., Pugnaloni, A., Belmonte, M.M., Biagini, G., Castaldini, C., (1993) Biomaterials, 14, p. 925; Muzzarelli, R.A.A., Mattiolibelmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., (1994) Biomaterials, 15, p. 1075; Madihally, S.V., Matthew, H.W.T., (1999) Biomaterials, 20, p. 1133; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., (2002) Biomaterials, 23, p. 3227; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., (2000) J Biomed Mater Res, 51, p. 586; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J Biomed Mater Res Part A, 75, p. 387; Muzzarelli, R.A.A., Muzzarelli, C., (2002) Chitosan in Pharmacy and Chemistry, p. 233. , Muzzarelli, R. A. A.; Muzzarelli, C., Eds.; Atec Edizioni: Grottammare, Italy; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J Controlled Release, 78, p. 187; Ho, M.H., Wang, D.M., Hsieh, H.J., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., (2005) Biomaterials, 26, p. 3197; Amaral, I.F., Cordeiro, A., Sampaio, P., Barbosa, M.A., J Biomat Sci: Polym, , accepted; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Hidaka, Y., Ito, M., Mori, K., Yagasaki, H., Kafrawy, A.H., (1999) J Biomed Mater Res, 46, p. 418; Mucalo, M.R., Yokogawa, Y., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., (1995) J Mater Sci: Mater Med, 6, p. 658; Tanahashi, M., Matsuda, T., (1997) J Biomed Mater Res, 34, p. 305; Yokogawa, Y., Rayes, J.P., Mucalo, M.R., Toriyama, M., Kawamoto, Y., Suzuki, T., Nishizawa, K., Kamayama, T., (1997) J Mater Sci: Mater Med, 8, p. 407; Granja, P.L., Barbosa, M.A., Pouysegu, L., De Jeso, B., Rouais, F., Baquey, C., (2001) J Mater Sci, 36, p. 2163; Amaral, I.F., Granja, P.L., Barbosa, M.A., (2005) J Biomater Sci Polym Ed, 16, p. 1575; Amaral, I.F., Granja, P.L., Barbosa, M.A., (2004) Key Eng Mater, 254, p. 577; Granja, P.L., Pouysegu, L., Petraud, M., De Jeso, B., Baquey, C., Barbosa, M.A., (2001) J Appl Polym Sci, 82, p. 3341; Touey, G.P., Kingsport, T., (1956), U.S. Pat. 2,759,924Fricain, J.C., Granja, P.L., Barbosa, M.A., De Jeso, B., Barthe, N., Baquey, C., (2002) Biomaterials, 23, p. 971; Sakaguchi, T., Horikoshi, T., Nakajima, A., (1981) Agric Biol Chem, 45, p. 2191; Sakairi, N., Shirai, A., Miyazaki, S., Tashiro, H., Tsuji, Y., Kawahara, H., Yoshida, T., Tokura, S., (1998) Kobunshi Ronbunshu, 55, p. 212; Lee, Y.M., Shin, E.M., (1991) J Membr Sci, 64, p. 145; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., (1999) Biomaterials, 20, p. 879; Yokogawa, Y., Nishizawa, K., Nagata, F., Kamayama, T., (1999) Bioceramics, p. 129. , Ohgushi, H.; Hastings, G. W.; Yoshikawa, T., Eds.; World Scientific: Singapore; Anselme, K., (2000) Biomaterials, 21, p. 667; Northup, S.J., Cammack, J., (1999) Handbook of Biomaterials Evaluation: Scientific, Technical, and Clinical Testing of Implant Materials, p. 325. , Recum, A. F., Ed.; Taylor & Francis: Philadelphia, PA; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., (2001) Polymer, 42, p. 3569; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., (1996) Carbohydr Polym, 29, p. 63; Grundke, K., Bogumil, T., Werner, C., Janke, A., Poschel, K., Jacobasch, H.J., (1996) Colloids Surf A, 116, p. 79; Kerkeb, M.L., Gonzalezcaballero, F., Chibowski, E., (1993) J Colloid Interface Sci, 159, p. 439; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) Surface and Interfacial Aspects of Biomedical Polymers, p. 249. , Andrade, J. D., Ed.; Plenum: New York; Owens, D.K., Wendt, R.C., (1969) J Appl Polym Sci, 13, p. 1741; Berridge, M.V., Tan, A.S., McCoy, K.D., Wang, R., (1996) Biochemica, 4, p. 14; Mosmann, T., (1983) J Immunol Methods, 65, p. 55; Huang, R.Y.M., Moon, G.Y., Pal, R., (2001) J Membr Sci, 184, p. 1; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., (2000) Colloids Surf B, 19, p. 367; MacDonald, D.E., Markovic, B., Allen, M., Somasundaran, P., Boskey, A.L., (1998) J Biomed Mater Res, 41, p. 120; Roberts, G.A.F., (1992) Chitin Chemistry, p. 350. , Macmillan: London; Andrade, J.D., (1992) Clin Mater, 11, p. 19; Wu, S., (1982) Polymer Interface and Adhesion, , Marcel Dekker: New York; Granja, P.L., Pouysegu, L., Deffieux, D., Daude, G., De Jeso, B., Labrugere, C., Baquey, C., Barbosa, M.A., (2001) J Appl Polym Sci, 82, p. 3354; Ratner, B.D., Caster, D.G., (1997) Surface Analysis - The Principal Techniques, p. 43. , Vickerman, J. C., Ed.; Wiley: Chichester, England; Barnes, A., Corkhill, P.H., Tighe, B.J., (1988) Polymer, 29, p. 2191; Domard, A., (1997) Advances in Chitin Science, p. 410. , Domard, A.; Roberts, G.; Vårum, K., Eds.; Jacques André: Lyon, France; Denuziere, A., Ferrier, D., Damour, O., Domard, A., (1998) Biomaterials, 19, p. 1275; Wang, X.H., Ma, J.B., Feng, Q.L., Cui, F.Z., (2002) Biomaterials, 23, p. 4591; Wang, X.H., Ma, J.B., Wang, Y.N., He, B.L., (2002) Biomaterials, 23, p. 4167; Hamano, T., Chiba, D., Nakatsuka, K., Nagahata, M., Teramoto, A., Kondo, Y., Hachimori, A., Abe, K., (2002) Polym Adv Technol, 13, p. 46
Keywords: Atomic force microscopy; Atomic force microscopy (AFM); Biocompatibility; Biological applications; Biological applications of polymers; Biomaterials; Chitin; chitosan; Chitosan membranes; grafting; Grafting (chemical); Osteoblastic cells; Phosphorylation; Polymeric membranes; polysaccharide; Polysaccharides; surface property; toxicity; Urea

Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike® synthetic bone graft - Gutierres, M.; Hussain, N.S.; Lopes, M.A.; Alfonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Orthopaedic ResearchJ. Orthop. Res., 2006)
Synthetic bone grafts provide an alternative to autografts and allografts. Bonelike® is a patented synthetic bone graft that mimics the mineral composition of bone. The aim of the present work was to assess the biological behavior of Bonelike® graft in humans, before using the material in orthopedic applications of bone regeneration, for example, in opening wedge high tibial osteotomies for medial knee osteoarthritis. Bonelike® granules were implanted in cortical bone of 11 patients undergoing osteotomies, and new bone formation, osteoconductive properties, and resorption characteristics of the granules were analyzed. The granules ranged from 500 to 1000 μm and were implanted in the lateral aspect of the tibia. The patients' mean age was 59 years (range 48 to 70 years); there were eight women and three men, all suffering from medial compartment osteoarthritis of the knee. At surgery, a 1 × 1 × 1-cm cortical defect was created 3 cm distal to the entry point of the screws, in line with the long axis of tibia. The implanted Bonelike® graft sample was extracted for analysis during removal of the metallic prosthesis after implantation times of 6, 9, and 12 months. Radiological follow-up, scanning electron microscopy, histological analysis, and histomorphometric measurements were conducted on the retrieved samples to assess bone regeneration in the defect area. Osteoconductive capacity was demonstrated by extensive mature bone formation around the implanted granules and high levels of percentage bone-to-graft contact (from 67-84%). Bonelike® acted as an excellent bioactive scaffold, allowing the migration, proliferation, and differentiation of bone cells on its surface, and therefore regeneration of the defects was achieved in a rapid, controlled manner. Our results suggest that Bonelike® graft is an excellent candidate for orthopedic applications where rapid new bone formation is a fundamental requirement. © 2006 Orthopaedic Research Society. Published by Wiley Periodicals, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JOREDdoi: 10.1002/jor.20117Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; DEMM, Faculty of Engg., University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: Bonelike; JSM 630IF, JeolManufacturers: JeolReferences: Peter, P., Heinrich, R., Meinrad, P., (2003) Orthopaedic Issues in Osteoporosis, , YH An, editor. Boca Raton, FL: CRC Press;Hench, L.L., Wilson, J., (1999) An Introduction to Bioceramics, , Singapore: World Scientific Publishing Co. Pvt. Ltd; Corpe, R.S., Steflik, D.E., Whitehead, R.Y., Correlative experimental animal and human clinical retrieval evaluations (2000) Crit Rev Biomed Eng, 28, pp. 395-398; Kitsugi, T., Yamamuro, T., Nakamura, T., Four calcium phosphate ceramics as bone substitutes for non-weight bearing (1993) Biomaterials, 14, pp. 216-224; Koshino, T., Murase, T., Takagi, T., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; LeGeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, pp. 4-45. , Meyers HM, editor. New York: Karger; Macdonald, D.E., Betts, F., Stranick, M., Physicochemical study of plasma-sprayed hydroxyapatite-coated implants in humans (2001) J Biomed Mater Res, 54, pp. 480-490; Oonishi, H., Yamamoto, M., Ishimaru, H., The effect of hydroxyapatite coating on bone growth into porous titanium alloy implants (1989) J Bone Surg Br, 71, pp. 213-216; Thomas, K.A., Hydroxyapatite coatings (1994) Orthopedics, 17, pp. 267-278; Doron, H., Amy, L.L., Bone graft substitutes (2003) Oper Tech Plastic Reconstruct Surg, 9, pp. 151-160; Write, S., The bone-graft market in Europe. Commentary extracted from a report entitled "Emerging technologies in orthopedics I.: Bone graft substitutes, bone growth stimulators and bone growth factors" (1999), pp. 591-595. , London: Datamonitor plcBotelho, C.M., Brooks, R.A., Best, S.M., Biological and physical-chemical characterization of phase pure HA and si-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254, p. 845; Costa, M.A., Gutierres, M., Almeida, L., In vitro mineralisation of human bone marrow cells cultured on bonelike® (2004) Key Eng Mater, 254-256, pp. 821-824; Gutierres, M., Hussain, N.S., Afonso, A., Biological behaviour of bonelike® graft Implanted in the tibia of humans (2005) Key Eng Mater, 284-286, pp. 1041-1044; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20, pp. 2085-2090; Lopes, M.A., Silva, R.F., Monteiro, F.J., Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications (2000) Biomaterials, 21, pp. 749-754; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21, pp. 1905-1910; Santos, J.D., Knowles, J.C., Reis, R.L., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Felson, D.T., Naimark, A., Anderson, J., The prevalence of knee osteoarthritis in the elderly: The Framingham Study (1987) Arthritis Rheum, 30, pp. 914-918; Guincamp, C., Pap, T., Schedel, J., Gene therapy in osteoarthritis (2000) Joint Bone Spine, 67, pp. 570-571; Marc, F., Serge, P., Mario, M.L.C., Assessment of the test-retest reliability and construct validity of a modified lequesne index in knee osteoarthritis (2003) Joint Bone Spine, 70, pp. 520-525; Pendleton, A., Arden, N., Dougados, M., EULAR recommendations for the management of knee osteoarthritis: Report of a task force of the Standing Committee for International Clinical Studies Including Therapeutic Trials (ESCISIT) (2000) Ann Rheum Dis, 59, pp. 936-944; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered hydroxyapatite compositions and method for the preparation thereof (1999) Eur. Pat. WO 0068164; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J Bone Joint Surg Am, 47, p. 984; Hing, K.A., Assessment of porous hydroxyapatite for bone replacement (1996), (Ph D Thesis). London: University of LondonLopes, M.A., Knowles, J.C., Santos, J.D., Direct and indirect effects of P 2O 5-glass reinforced-hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Knowles, J.C., Santos, J.D., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology - A Text and Atlas, , 3rd ed. Baltimore, MD: Williams & Wilkins; Lobato, J.V., Hussain, N.S., Botelho, C.M., Assessment of the potential of Bonelike® graft for bone regeneration by using an animal model (2005) Key Eng Mater, 284-286, pp. 877-880; Duarte, F., Lopes, M.A., Santos, J.D., Bonelike® composites for the regeneration of bone lesions (2004) Mater Sci Forum, 455-456, pp. 370-373; Laurencin, C.T., (2003) Bone Graft Substitutes, , West Conshohocken, PA: ASTM International
Keywords: adult; aged; article; Bone; Bone and Bones; bone cell; bone conduction; bone development; Bone graft; bone prosthesis; bone radiography; Bone Regeneration; bone screw; Bone Substitutes; bone transplantation; Bonelike®; cell differentiation; cell migration; cell proliferation; Clinical applications; clinical article; controlled study; Female; follow up; Histological analysis; histology; human; Humans; knee osteoarthritis; male; Microscopy, Electron, Scanning; Middle Aged; morphometrics; orthopedics; ossification; Osteoconduction; Osteogenesis; osteolysis; Pathology; priority journal; Prostheses and Implants; prostheses and orthoses; prosthesis material; Scanning electron microscopy; surgical technique; Synthetic bone graft; tibia osteotomy; ultrastructure

Human osteoblast response to silicon-substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Best, S.M.; Lopes, M.A.; Santos, J.D.; Rushton, N.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
Human osteoblasts were cultured on hydroxyapatite (HA), 0.8 wt % silicon substituted hydroxyapatite (Si-HA) and 1.5 wt % Si-HA discs. The influence of these substrates on cell behaviour in vitro was assessed by measuring total protein in the cell lysate and the production of several phenotypic markers: collagen type I (COL 1), alkaline phosphatase (ALP), osteocalcin (OC), and the formation of bone mineral. After 7 days, β-glycerophosphate and physiological levels of hydrocortisone were added to the culture medium to stimulate cell differentiation and mineral production. There was a significantly higher production of ALP on 1.5 wt % Si-HA at day 7 following which, the addition of hydrocortisone promoted the differentiation of cells on the other two substrates. Hydrocortisone addition also decreased the production of OC. During the period, when hydrocortisone was present, no significant difference in behavior was seen between cells on Si-HA and HA; however, following removal of hydrocortisone, cells responded to 0.8 wt % Si-HA with a significant increase in protein production. Using fluorescence microscopy, nodular structures labeled with tetracycline were observed on the surface of all substrates after 21 days. These structures were deposited on areas of high cell density but were not related to the presence or level of silicon in the substrate. These results indicate that human osteoblasts are affected by the presence of silicon in the HA substrate and that the timing of these effects may be dependent upon the level of silicon substitution. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30806PubMed ID: 16871624Language of Original Document: EnglishCorrespondence Address: Brooks, R.A.; Orthopaedic Research Unit, Box 180, Addenbrooke's Hospital, Hills Road, Cambridge CB2 3QZ, United Kingdom; email: rb10003@cam.ac.ukChemicals/CAS: alkaline phosphatase, 9001-78-9; glycerol 2 phosphate, 17181-54-3; hydrocortisone, 50-23-7; hydroxyapatite, 1306-06-5, 51198-94-8; osteocalcin, 136461-80-8; silicon, 7440-21-3; tetracycline, 23843-90-5, 60-54-8, 64-75-5; Collagen Type I; Durapatite, 1306-06-5; ectonucleotide pyrophosphatase phosphodiesterase 1, EC 3.1.4.1; Minerals; Osteocalcin, 104982-03-8; Phosphoric Diester Hydrolases, EC 3.1.4.-; Pyrophosphatases, EC 3.6.1.-; Silicon, 7440-21-3References: Hench, L., Splinter, R., Allan, W., Greenlee, T., Bonding mechanism at the interface of ceramic prosthetic materials (1972) J Biomed Mater Res, 2, pp. 117-141;Ducheyne, P., Hench, L., Kagan, A., Martens, M., Burssens, A., Mulier, J., The effect of hydroxyapatite impregnation on skeletal bonding of porous coated implants (1980) J Biomed Mater Res, 14, pp. 225-237; Jarcho, M., Calcium phosphates ceramics as hard tissue prosthetics (1981) Clin Orthop, 157, pp. 259-278; Nakamura, T., Yamamuro, T., Higashi, S., Kokubo, T., Ito, S., A new glass-ceramic for bone replacement: Evaluation of its bonding to bone tissue (1985) J Biomed Mater Res, 19, pp. 685-698; Ducheyne, P., Bianci, P., Radin, S., Schepers, E., Bioactive materials: Mechanism and bioengineering considerations (1993) Bone-Bioactive Biomaterials, pp. 1-12. , Ducheyne P, Kokubo T, van Blitterswijik C, editors. Leiderdorp, The Netherlands: Reed Healthcare Communications; Patel, N., Best, S., Gibson, I.R., Hing, K., Damien, K., Bonfield, W., A comparative study on the in vivo behaviour of hydroxyapatite and silicon substituted hydroxyapatite granules (2002) J Mater Sci Mater Med, 13, pp. 1199-1206; Jha, L., Best, S., Santos, J., Gibson, I., Bonfield, W., Silicon-substituted apatites and process for the preparation thereof Worldwide Patent,PCT/GB97/02325 and US Patent0.9/147773, 1999Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Schwarz, K., Significance and functions of silicon in warm-blooded animals (1977) Proceedings of the 40th Nobel Symposium, , Bendz G, Lindquist I, editors. Biochemistry of Silicon and Related Problems. New York: Plenum; Lidingö, Sweden, August 23-26; Baxter, J., Rousseau, G., Benson, M., Garcea, R.L., Ito, J., Tomkins, G., Role of DNA and specific cytoplasmic receptors in glucocorticoid action (1972) Proc Natl Acad Sci USA, 69, p. 1892; Darley, W., Volcani, B., Role of silicon in diatom metabolism. A silicon requirement for deoxyribonucleic acid synthesis in diatom Cylindrotheca-fusiformis reimann and lewin (1969) Exp Cell Res, 58 (2-3), p. 334; Finkelstein, D., Butow, R., DNA-binding proteins in yeast. Effect of growth phase and mitochondrial-function (1976) Arch Biochem Biophys, 174, pp. 52-65; Volcani, B.E., Role of silicon in diatom metabolism and silicification (1977) Proceedings of the 40th Nobel Symposium, , Bendz G, Lindquist I, editors. Biochemistry of Silicon and Related Problems. New York: Plenum; Lidingo, Sweden, August 23-26; Werner, D., Regulation of metabolism by silicate in diatoms (1977) Proceedings of the 40th Nobel Symposium, , Bendz G, Lindquist I, editors. Biochemistry of Silicon and Related Problems. New York: Plenum; Lidingö, Sweden, August 23-26; Carlisle, E., Essentiality and function of silicon (1977) Proceedings of the 40th Nobel Symposium, , Bendz C, Lindquist I, editors. Biochemistry of Silicon and Related Problems New York: Plenum; Lidingo, Sweden, August 23-26; Carlisle, E., (1986) Silicon Biochemistry, , New York: Wiley; Schwarz, K., Milne, D., Growth-promoting effects of silicon in rats (1972) Nature, 239, p. 333; Seaborn, C., Nielsen, F., Dietary silicon affects acid and alkaline phosphatase and 45calcium uptake in bone of rats (1994) J Trace Elem Exp Med, 7, pp. 11-18; Reffitt, D., Ogston, N., Jugdaohsingh, R., Cheung, H., Evans, B., Thompson, R., Powell, J.J., Hampson, G.N., Orthosilicic acid stimulates collagen type I synthesis and osteoblastic differentiation in human osteoblast-like cells in vitro (2003) Bone, 32, p. 127; Shi, S., Kirk, M., Kahan, A., The role of type 1 collagen in the regulation of the osteoblast phenotype (1996) J Bone Miner Res, 11, pp. 1139-1145; Hildebrand, M., Higgins, D., Busser, K., Benjamin, E., Silicon-responsive cDNA clones isolated from the marine diatom Cylindrotheca fusiformis (1993) Gene, 132, pp. 213-218; Voronkov, M.G., Skorobogatova, V.J., Vugmeíster, E.K., Makarskii, V.V., Silicon in nuclei acids (1975) Dokl Biochem, 222, p. 29; Hench, L., Orcel, G., Physical-chemical and biochemical factors in silica sol-gel (1986) J Non-Cryst Solids, 82, pp. 1-10; Keting, P., Oursler, M., Wiegand, K., Bonde, S., Spelsberg, T., Riggs, L., Zeolite a increases proliferation, differentiation, and transforming growth factor production in normal adult human osteoblast-like cells in vitro (1992) J Bone Miner Res, 7, p. 1281; Gibson, I.R., Huang, J., Best, S.M., Bonfield, W., Enhanced in vitro cell activity and surface apatite layer formation on novel silicon-substituted hydroxyapatites (1999) Bioceramics, 12, pp. 191-194. , Ohgushi H, Hastings GW, Yoshikawa T, editors. Nara, Japan: World Scientific Publishing Company; Botelho, C.M., Brooks, R., Lopes, M.A., Santos, J.D., Best, S.M., Bonfield, W., Biological and physical-chemical characterization of phase pure HA and Si-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254-256, pp. 845-848; Botelho, C.M., Stokes, D., Brooks, K., Best, S., Lopes, M., Santos, J.D., Effect of human serum proteins on the surface of pure HA and Si-substituted HA: AFM and ESEM studies (2003) Mater Sci Forum, 455-456, pp. 378-382; Sakobar, A., Millet, P., Myer, B., Rushton, N., A rapid, quantitative assay for measuring alkaline phosphatase activity in osteoblastic cells in vitro (1994) Bone Miner, 27, pp. 57-67; Botelho, C.M., Lopes, M.A., Gibson, I.R., Best, S.M., Santos, J.D., Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy (XPS) (2002) J Mater Sci Mater Med, pp. 1123-1127; Lian, J., Stein, G., Aubin, J., Bone formation: Maturation and functional activities of osteoblast lineage cells (2003) Primer on the Metabolic Bone Diseases and Disorders of Mineral Metabolism, pp. 13-28. , Favus M, editor. Philadelphia: Lippincott; Boskey, A., Biomineralization: Conflicts, challenges and opportunities (1998) J Cell BiochemSuppl, 30-31, pp. 83-91; Jaiswal, N., Haynesworth, S., Caplan, A., Bruder, S., Osteogenic differentiation of purified culture-expanded human mesenchymal stem cells in vitro (1997) J Cell Biochem, 64, pp. 295-312; Baylink, D., Glucocorticoid-induced osteoporosis (1983) N Engl J Med, 309, pp. 306-308; Ireland, D., Bord, S., Beavan, S., Compston, J., Hydrocortisone increases the rate of differentiation of culture human osteoblasts (2004) J Cell Biochem, 91, pp. 594-601; Lian, J., Stein, G., Stein, J., Wijnen, A., Osteocalcin gene promoter: Unlocking the secrets for regulation of osteoblasts growth and differentiation (1998) J Cell BiochemSuppl, 30-31, pp. 62-72; Canalis, E., Mechanisms of glucocorticoid action in bone: Implications to glucocorticoid-induced osteoporosis (1995) J Clin Endocrinol Metab, 10, pp. 3441-3447; Delany, A., Gabbitas, B., Canalis, E., Cortisol down-regulates osteoblast α 1 (I) procollagen mRNA by transcriptional and post-transcriptional mechanisms (1995) J Cell Biochem, 57, pp. 488-494; Bellows, C., Aubin, J., Heersche, J., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Cheng, S., Zhang, S., Mohan, S., Eecanda, E., Eausto, A., Hunt, A., Canalis, E., Avioli, L.V., Regulation of insulin-like growth factors I and II and their binding proteins in human bone marrow stromal cells by dexamethasone (1998) J Cell Biochem, 71, pp. 449-458; Boskey, A., Paschalis, E., Matrix proteins and biomineralization (1999) Bone Engineering, pp. 44-62. , Davie J, editor. Toronto: Em Squared; Shiga, M., Kapila, Y., Zhang, Q., Hayami, T., Kapila, S., Ascorbic acid induces collagenase-1 in human periondontal ligament cells but not in MC3T3-E1 osteoblast-like cells: Potential association between collagenase expression and changes in alkaline phosphatase phenotype (2003) J Bone Miner Res, 18, pp. 67-77; Franceschi, R., Iyer, B., Cui, Y., Effects of ascorbic acid on collagen matrix formation ans osteoblast differentiation of murine MC3T3-E1 cells (1994) J Bone Miner Res, 9, pp. 843-854; Franceschi, R., Iyer, B., Relationship between collagen synthesis and expression of the osteoblast phenotype in MC3T3-E1 cells (1992) J Bone Miner Res, 7, pp. 235-246; Aronow, M., Gerstenfeld, E., Owen, T., Tassinari, M., Stein, G., Lian, J., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Physiol, 143, pp. 213-221; Chien, H., Lin, W., Cho, M., Interkukin-1b-induced release of matrix proteins into culture media causes inhibition of mineralization of nodules formed by periodontal ligament cells in vitro (1999) Calcif Tissue Int, 64, pp. 402-413; Botelho, C.M., Brooks, R.A., Kawai, T., Ogata, S., Ohtsuki, C., Lopes, M.A., Best, S.M., Bonfield, W., In vitro analysis of proteins adhesion to phase pure hydroxyapatite and silicon-substituted hydroxyapatite (2005) Key Eng Mater, 17, pp. 461-464; Kaji, T., Kawatani, R., Takata, M., Hoshino, T., Miyahara, T., Kozuka, H., Koizumi, F., The effects of cadmium, copper or zinc on formation of embryonic chick bone in tissue culture (1988) Toxicology, 50, pp. 303-316
Keywords: alkaline phosphatase; article; Biomarkers; bone mineral; cell activity; Cell culture; cell density; cell differentiation; cell function; cell lysate; cell marker; cell protein; Cells; Cells, Cultured; collagen type 1; Collagen type I; culture medium; Durapatite; Fluorescence microscopy; glycerol 2 phosphate; hormone determination; human; human cell; Human osteoblasts; Humans; Hydrocortisone; hydroxyapatite; in vitro study; Minerals; Nodular mineral formation; osteoblast; Osteoblasts; osteocalcin; Osteocalcin (OC); phenotype; Phosphoric Diester Hydrolases; protein analysis; protein synthesis; Pyrophosphatases; Silicon; Substitution reactions; Substrates; Tetracycline; β-glycerophosphate

An improved management model for tracking multiple features in long image sequences - Pinho, R.R.; Tavares, J.M.R.S.; Correia, M.V. (WSEAS Transactions on Information Science and ApplicationsWSEAS Trans. Inf. Sci. Appl., 2006)
In this paper we present a management model to deal with the problem of tracking a large number of features during long image sequences. Some usual difficulties are related to this problem: features may be temporarily occluded or might even have disappeared definitively; the computational cost involved should always be reduced to the strictly necessary. The proposed Net Present Value (NPV) model, based on the economic Theory of Capital, considers the tracking of each missing feature as an investment. Thus, using the NPV criterion, with adequate receipt and outlay functions, each occluded feature may be kept on tracking or it may be excluded of the tracking process depending on its historical behavior. This methodology may be applied to any tracking system as long as the tracking results may be evaluated in each temporal step. Experimental results, both on synthetic and real image sequences, which validate our model, will be also presented.
Keywords: Computer vision; Costs; Feature extraction; Image sequences; Imaging systems; Management; Management model; Motion estimation; Net Present Value (NPV); Occlusion; Tracking; Tracking (position); Tracking multiple features

In vivo performance of biodegradable calcium phosphate glass ceramics using the rabbit model: Histological and SEM observation - Dias, A.G.; Lopes, M.A.; Santos, J.D.; Afonso, A.; Tsuru, K.; Osaka, A.; Hayakawa, S.; Takashima, S.; Kurabayashi, Y. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2006)
Two MK5 (45CaO-45P 2O 5-5MGO-5K 2O, in mol% and MT13 (45CaO-37P 2O 5-5MgO-13TiO 2, in mol%) glasses are prepared in the meta- and pyrophosphate regions and crystallized to obtain MK5B and MT13B, respectively. MK5B was obtained by controlled crystallization, and MT13B by powder sintering. As a result of these heat treatment processes, the crystalline phases precipitated in the glassy matrix are KCa(PO 3) 3, β-Ca(PO 3) 2, β-Ca 2P 2O 7 and Ca 4P 6O 19 phases for MK5B and CaTi 4(PO 4) 6, TiP 2O 7, α- and β-Ca 2P 2O 7 phases for MT13B. To assess the in vivo biological behavior of these glass ceramics, a mixed granulometry in the range 250-355 μm and 355-425 μm with a ratio of 1/1 was implanted for 2, 4, and 12 weeks in the tibiae of Japanese white rabbits. The results showed that the in vivo behavior was strongly affected by their solubility. All implanted materials, MK5B and MT13B, and β-tricalcium phosphate (β-TCP) as control material, showed signs of degradation in vivo. However, the levels of degradation were quite different throughout the implantation periods. The highest degradation was observed for MK5B glass ceramic and the lowest for MT13B with β-TCP in-between. All implanted materials allow for new bone formation in the bone defect area. At the longest implantation period (12 weeks), the MT13B and β-TCP materials were almost completely surrounded by new bone tissue, whereas MK5B showed some unfilled spaces. This behavior is discussed in terms of the high degradation observed in previous studies. © 2006 SAGE Publications.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: JBAPEdoi: 10.1177/0885328206052466Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; Bone Substitutes; calcium phosphate, 10103-46-5; Calcium Phosphates; CeramicsReferences: Parikh, S.N., Bone Graft Substitutes in Modern Orthopedics (2002) Orthopedics, 25 (11), pp. 1301-1309;Tomford, W.W., Bone Allografts: Past, Present and Future (2000) Cell and Tissue Banking, 1, pp. 105-109; Betz, R.R., Limitations of Autograft and Allograft: New Synthetic Solutions (2002) Orthopedics, 25 (5), pp. S561-S570; Lane, J.M., Tomin, E., Bostrom, M.P.G., Biosynthetic Bone Grafting, Clinical Orthopaedics and Related Research (1999) Supplement S, 367, pp. S107-S117; Gazdag, A.R., Lane, J.M., Glaser, D., Forster, R.A., Alternatives to Autogenous Bone Graft: Efficacy and Indications (1995) Journal of the American Academy of Orthopaedic Surgeons, 3 (1); Vaccaro, A.R., The Role of the Osteoconductive Scaffold in Synthetic Bone Grafts (2002) Orthopedics, 25 (5), pp. S571-S578; Damien, C.J., Parsons, J.R., Bone-Graft and Bone-Graft Substitutes - A Review of Current Technology and Applications (1991) Journal of Applied Biomaterials, 2 (3), pp. 187-208; Porter, A.E., Patel, N., Skepper, J.N., Best, S.M., Bonfield, W., Comparison of in vivo Dissolution Processes in Hydroxyapatite and Silicon-substituted Hydroxyapatite Bioceramics (2003) Biomaterials, 24 (25), pp. 4609-4620; Raynaud, S., Champion, E., Lafon, J.P., Bernache-Assollant, D., Calcium Phosphate Apatites with Variable Ca/P Atomic Ratio III Mechanical Properties and Degradation in Solution of Hot Pressed Ceramics (2002) Biomaterials 23, 4, pp. 1081-1089; Klein, C., Wolke, J.G.C., Deblieckhogervorst, J.M.A., Degroot, K., Features of Calcium-Phosphate Plasma-Sprayed Coatings - An in-vitro Study (1994) Journal of Biomedical Materials Research, 28 (8), pp. 961-967; Brow, R.K., Review: The Structure of Simple Phosphate Glasses (2000) Journal of Non-Crystalline Solids, 263 (1-4), pp. 1-28; Shelby, J.E., (1997) Introduction to Glass Science and Technology, , The Royal Society of Chemistry, UK; Fini, M., Giardino, R., In vitro and in vivo Tests for the Biological Evaluation of Candidate Orthopedic Materials: Benefits and Limits (2003) Journal of Applied Biomaterials & Biomechanics, 1, pp. 155-163; Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, F.J., (1996) Biomaterials Science: An Introduction to Materials in Medicine, , Academic Press; Dias, A.G., Lopes, M.A., Gibson, I.R., Santos, J.D., In vitro Degradation Studies of Calcium Phosphate Glass Ceramics Prepared by Controlled Crystallization (2003) Journal of Non-Crystalline Solids, 330 (1-3), pp. 81-89; Dias, A.G., Lopes, M.A., Santos, J.D., Protein Adsorption Effect on in vitro Acellular Biodegradation of CaO-P 2O 5 Glass Ceramics (2004) Advanced Materials Forum, 455-456, pp. 398-401; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., In situ Thermal and Structural Characterization of Bioactive Calcium Phosphate Glass Ceramics Containing TiO 2 and MgO Oxides: HT-XRD Studies (2005) Journal of Non-Crystalline Solids, 351, pp. 810-817; Dias, A.G., Tsuru, K., Hayakawa, T., Lopes, M.A., Santos, J.D., Osaka, A., Crystallisation Studies of Biodegradable CaO-P 2O 5 Glass with MgO and TiO 2 for Bone Regeneration Applications (2004) Glass Technology, 45 (2), pp. 78-79; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue Response in the Femur of Rabbits after Implantation of a New Calcium Titanium Phosphate Composition (2000) Key Engineering Materials, 192, pp. 383-386; Kitsugi, T., Yamamuro, T., Nakamura, T., Masanori, O., Transmission Electron Microscopy Observations at the Interface of Bone and Four Types of Calcium Phosphate Ceramics with Different Calcium/ Phosphorous Molar Ratios (1995) Biomaterials, 16 (14), pp. 1101-1107; Chun, S., Jeong, J.H., Kim, K-H., Kim, S., Biodegradation Study of Amorphous and Crystalline Calcium Metaphosphate in the SBF and Tris-buffer Solution (2000) Key Engineering Materials, 192, pp. 131-134; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., Biodegradation Study of Potassium Calcium Metaphosphate in the SBF and Tris-buffer Solution (2002) Key Engineering Materials, 218, pp. 149-152; Lin, F.H., Liao, C.J., Chen, K.S., Sun, J.S., Liu, H.C., Degradation Behaviour of a New Bioceramic: Ca 2P 2O 7 with Addition of Na 4P 2O 7 · 10H 2O (1997) Biomaterials, 18 (13), pp. 915-921; Koerten, H.K., van der Meulen, J., Degradation of Calcium Phosphate Ceramics (1999) Journal of Biomedical Materials Research, 44 (1), pp. 78-86; Kwon, S.H., Jun, Y.K., Hong, S.H., Kim, H.E., Synthesis and Dissolution Behavior of Beta-TCP and HA/Beta-TCP Composite Powders (2003) Journal of the European Ceramic Society, 23 (7), pp. 1039-1045; Lu, J.X., Gallur, A., Flautre, B., Anselme, K., Descamps, M., Thierry, B., Comparative Study of Tissue Reactions to Calcium Phosphate Ceramics among Cancellous, Cortical, and Medullar Bone Sites in Rabbits (1998) Journal of Biomedical Materials Research, 42 (3), pp. 357-367; Yuan, H.P., De Bruijn, J.D., Li, Y.B., Feng, J.Q., Yang, Z.J., De Groot, K., Zhang, X.D., Bone Formation Induced by Calcium Phosphate Ceramics in Soft Tissue of Dogs: A Comparative Study Between Porous α-TCP and Β-TCP (2001) Journal of Materials Science-Materials in Medicine, 12 (1), pp. 7-13; Jiaxi, L., Michel, D., Jacques, D., Gilles, K., Pierre, H., Jacques, L., The Biodegradation Mechanism of Calcium Phosphate Biomaterials in Bone Journal of Biomedical Materials Research (Applied Biomaterials), 63, pp. 408-412; Legeros, R.Z., Biodegradation and Bioresorption of Calcium Phosphate Ceramics (1993) Clinic Materials, 14, pp. 65-88; Yli-Urpo, H., Vallittu, P.K., Narhi, T.O., Forsback, A.P., Vakiparta, M., Release of Silica, Calcium, Phosphorus, and Fluoride from Glass Ionomer Cement Containing Bioactive Glass (2004) Journal of Biomaterials Applications, 19 (1), pp. 5-20; John, A., Varma, H.K., Kumari, T.V., Surface Reactivity of Calcium Phosphate based Ceramics in a Cell Culture System (2003) Journal of Biomaterials Applications, 18 (1), pp. 63-78; Dias, A.G., Lopes, M.A., Gibson, I.R., Skakle, J.M.S., Tsuru, K., Hayakawa, S., Osaka, A., Santos, J.D., Studies of Calcium Phosphate Glass Ceramic Containing TiO 2 and MgO Ions: Dissolution Behavior, , vitro (submitted)
Keywords: Absorbable Implants; animal; Animals; article; Biodegradable glass ceramics; biodegradable implant; Biodegradation; bone prosthesis; Bone Substitutes; bone tissue; Calcium Compounds; calcium phosphate; Calcium phosphates; ceramics; chemistry; disease model; Disease Models, Animal; glass; Glass ceramics; histology; Imaging techniques; In vivo testing; materials testing; Optical microscopy; Pathology; rabbit; Rabbits; Scanning electron microscopy; tibia fracture; Tibial Fractures; Tissue; treatment outcome; X ray diffraction analysis

The influence of functional groups of self-assembled monolayers on fibrous capsule formation and cell recruitment - Barbosa, J.N.; Madureira, P.; Barbosa, M.A.; Águas, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The contribution of the surface chemistry of an implant to the thickness of the fibrous capsule formed after implantation was herein investigated. For that, self-assembled monolayers (SAMs) of alkanethiols on gold with different terminal functional groups (COOH, OH, and CH 3) were used. These surfaces were implanted in subcutaneous air pouches of BALB/c mice and the ensuing fibrous capsules were evaluated and compared with the initial inflammatory response caused by the implant. The thickness of the fibrous capsules that are under organization around the implant was measured 1 week after implantation by histology. Inflammatory exudates were collected from the air pouches 24 h after the implantation of SAMs and were analyzed by flow cytometry. A significant increase in the thickness of fibrous capsules was seen around implanted CH 3-terminated SAMs, and also in gold surfaces, in comparison with the air pouch wall of sham-operated mice and of COOH- and OH-covered SAMs. The CH 3-coated implants also recruited higher numbers of inflammatory cells; this enhancement involved a significant number of Mac-1 + cells. Our data indicate that implant surfaces coated with CH 3 induce thick fibrous capsules and this may be the result of the stronger inflammatory effect of CH 3 in comparison with COOH or OH chemical groups. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30602Language of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; thiol derivative, 13940-21-1; Biocompatible Materials; Gold, 7440-57-5; Sulfhydryl CompoundsReferences: Babensee, J.E., Anderson, J.M., McIntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliv Rev, 33, pp. 111-139;Anderson, J.M., In vivo biocompatibility of implantable delivery systems and biomaterials (1994) Eur J Pharm Biopharm, 40, pp. 1-8; Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110; Tang, L., Eaton, J.W., Inflammatory responses to biomaterials (1995) Am J Clin Pathol, 103, pp. 466-471; Mrksich, M., Whitesides, G.M., Interactions of SAM's with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrkisich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiences for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Castro, A.G., Esaguy, N., Macedo, P.M., Águas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Isaji, M., Momose, Y., Naito, J., Enhancement of inflammatory reactions in a non-immunological air pouch model in rats (1989) Br J Exp Pathol, 70, pp. 705-716; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on cibacron blue F3G-A immobilized onto oligo(ethylene glycol)-terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14, pp. 945-954; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Thomsen, P., Gretzer, C., Macrophage interactions with modified materials surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Tsai, M., Lin, J., Surface characterization and platelet adhesion studies of self-assembled monolayers with phosphonate ester and phosphonic acid functionalities (2001) J Biomed Mater Res, 55, pp. 554-565; Ostuni, E., Yan, L., Whitesides, G.M., The interaction of proteins and cells with self-assembled monolayers of alkanethiolates on gold and silver (1999) Colloids Surf B, 15, pp. 3-30; Yang, S., Ren, W., Park, Y., Sieving, A., Hsu, S., Nasser, S., Wooley, P.H., Diverse cellular and apoptotic responses to variant shapes of UHMWPE particles in a murine model of inflammation (2002) Biomaterials, 23, pp. 3535-3543; Sieving, A., Wu, B., Mayton, L., Nasser, S., Wooley, P.H., Morphological characteristics of total joint arthroplasty-derived ultrahigh molecular weight polyethylene (UHMWPE) wear debris that provoke inflammation in a murine model of inflammation (2003) J Biomed Mater Res A, 64, pp. 457-464; Barbosa, J.N., Barbosa, M.A., Águas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold (2004) Biomaterials, 25, pp. 2557-2563; Anderson, D.C., Springer, T.A., Leukocyte adhesion deficiency: An inherited defect in the Mac-1, LFA-1 and p150, 95 glycoproteins (1987) Annu Rev Med, 38, pp. 175-184; Murphy, R.T., Foley, J.B., Crean, P., Walsh, M.J., Reciprocal activation of leukocyte-endothelial adhesion molecules in acute coronary syndromes (2003) Int J Cardiol, 90, pp. 247-252; Tang, L., Wu, Y., Timmons, R.B., Fibrinogen adsorption and host tissue responses to plasma functionalized surfaces (1998) J Biomed Mater Res, 42, pp. 156-163; Barbosa, J.N., Madureira, P., Barbosa, M.A., Águas, A.P., The attraction of Mac-1 + phagocytes during acute inflammation by methyl-coated self-assembled monolayers (2005) Biomaterials, 26, pp. 3021-3027
Keywords: animal; animal cell; animal experiment; animal model; animal tissue; Animals; article; Bagg albino mouse; Biocompatible Materials; biomaterial; chemistry; controlled study; flow cytometry; functional group; gold; histology; implantation; Inflammation; male; Mice; Mice, Inbred BALB C; Monolayers; mouse; nonhuman; Self assembly; Self-assembled monolayers; Sulfhydryl Compounds; Surface chemistry; thiol derivative; tissue reaction; Tissue responses

Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bernardes, J. (Physiological MeasurementPhysiol. Meas., 2006)
The effect of foetal heart rate (FHR) acquisition mode on linear and nonlinear parameters is still largely unknown. In 33 normal labouring women, FHR signals were acquired simultaneously by an external ultrasound sensor applied to the maternal abdomen and an internal scalp electrode, in the minutes preceding delivery. For each case, the initial and final 5, 10 and 20 min segments were analysed, considering FHR signals at a frequency of 4 Hz (the frequency at which they are transmitted by the majority of commercialized foetal monitors). Several time and frequency domain linear and nonlinear FHR indices were computed in these segments, namely mean FHR, very low frequency (VLF), low frequency (LF), high frequency (HF), approximate entropy (ApEn) and sample entropy (SampEn). Parametric confidence intervals, statistical tests and correlation coefficients were calculated in order to evaluate the effect of internal versus external FHR monitoring modes on the considered indices. The whole evaluation was repeated using FHR signals at a frequency of 2 Hz. Most time domain linear indices were similar with external and internal monitoring in the initial and final segments of the tracings. However, linear frequency domain indices were poorly correlated in the final segments and had significantly different mean values in the initial segments. Nonlinear indices were significantly different in both initial and final segments. The correlation between 4 and 2 Hz sampled parameters was high for both linear and nonlinear indices (most correlation coefficient values ranging between 0.95 and 1) but nonlinear index values were significantly higher at 2 Hz. In conclusion, the mode used to acquire FHR signals and the sampling rate employed can significantly affect most FHR indices. © 2006 IOP Publishing Ltd.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: PMEAEdoi: 10.1088/0967-3334/27/3/008PubMed ID: 16462016Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade Do Porto, Porto, Portugal; email: hernani.goncalves@fc.up.ptReferences: Ayres-De-Campos, D., Bernardes, J., Garrido, A., Marques-De-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Matern. Fetal Med., 9 (5), pp. 311-318;Ayres-De-Campos, D., Bernardes, J., Reynolds, A., Saraiva, J.P., Santos, C., Pereira-Leite, L., Computer evaluation of internal versus external FHR monitoring in the minutes preceding delivery (2000) Int. J. Gynecol. Obstet., 70, pp. 60-B61; Ayres-De-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto ®multicentre validation study (2005) Eur. J. Obstet. Gynecol. Reprod. Biol., 118 (1), pp. 52-60; Bakker, P.C., Colenbrander, G.J., Verstraeten, A.A., Geijn, V., The quality of intrapartum fetal heart rate monitoring (2004) Eur. J. Obstet. Gynecol. Reprod. Biol., 116 (1), pp. 22-27; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int. J. Gynecol. Obstet., 62 (2), pp. 141-147; Bernardes, J., Costa-Pereira, A., The effect of different sampling intervals on the measurement of intrapartum fetal heart rate variability (1997) Obstet. Gynecol., 90 (2), pp. 318-319; Bernardes, J., Garrido, A., Computerized fetal heart rate analysis in labour based on 2-s sampling. Can it proceed with confidence? (1995) Eur. J. Obstet. Gynecol. Reprod. Biol., 63 (1), pp. 105-107; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J. Perinat. Med., 19, pp. 61-65; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Van Geijn, H.P., Pereira-Leite, L., The Porto system (1994) A Critical Appraisal of Fetal Surveillance, pp. 315-324; Boog, G., Analyse informatisée du rythme cardiaque fetal au cours de la grosssesse et de l'accouchement (2004) Encyclopédie Médico-Chirurgicale, 148; Boos, A., Jagger, M.H., Paret, G.W., Hausmann, J.W., A new, lightweight fetal telemetry system (1995) Hewlett-Packard J., pp. 82-93; Carter, M.C., Signal processing and display-cardiotocographs (1993) Br. J. Obstet. Gynaecol., 100, pp. 21-23; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J. Matern. Fetal Invest., 8, pp. 23-26; Chang, A., Sahota, D.S., Reed, N.N., James, D.K., Mohajer, M.P., Computerised fetal heart rate analysis in labour-effect of sampling rate (1995) Eur. J. Obstet. Gynecol. Reprod. Biol., 59 (2), pp. 125-129; Court, D.J., Parer, J.T., Experimental studies of fetal asphyxia and fetal heart rate interpretation (1984) Research in Perinatal Medicine, pp. 113-169; Dawes, G., Computerized fetal heart rate analysis (1994) A Critical Appraisal of Fetal Surveillance, pp. 311-314; Dawes, G.S., Moulden, M., Sheil, O., Redman, C.W.G., Approximate entropy, a statistic of regularity, applied to fetal heart rate data before and during labour (1992) Obstet. Gynecol., 80, pp. 763-768; Dawes, G.S., Moulden, M., Redman, C.W., Criteria for the design of fetal heart rate analysis systems (1990) Int. J. Biomed. Comput., 25 (4), pp. 287-294; Di Renzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Indraccolo, R., Cosmi, E.V., Fractal analysis: A new method for evaluating fetal heart rate variability (1996) J. Perinat. Med., 24, pp. 261-269; Echeverria, J.C., Hayes-Gill, B.R., Crowe, J.A., Woolfson, M.S., Croaker, G.D., Detrended fluctuation analysis: A suitable method for studying fetal heart rate variability? (2004) Physiol. Meas., 25 (3), pp. 763-774; Felgueiras, C., Marques-De-Sá, J.P., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed. Eng., 36, pp. 197-201; Felgueiras, C.S., Marques-De-Sá, J.P., Bernardes, J., Gama, S., On the reconstruction of fetal heart rate sequences (1996) Actas Do 4° Congresso Português de Engenharia Biomédica-BioEng'96, pp. 61-vii65; Fukushima, T., Flores, C.A., Hon, E.H., Davidson Jr., E.C., Limitations of autocorrelation in fetal heart rate monitoring (1985) Am. J. Obstet. Gynecol., 153, pp. 685-692; Fusheng, Y., Bo, H., Qingyu, T., Approximate entropy and its application in biosignal analysis (1998) Nonlinear Biomedical Signal Processing-Volume II: Dynamical Analysis and Modelling, pp. 72-91; Gough, N.A., Fractal analysis of fetal heart rate variability (1993) Physiol. Meas., 14 (3), pp. 309-315; Hayes, M., (1996) Statistical Digital Signal Processing and Modelling; Hewlett-Packard, (1993) Hewlett-Packard Series 50 Service Manual, M1351A and 1353A; Hirsch, M., Karin, J., Akselrod, S., Heart rate variability in the fetus (1995) Heart Rate Variability, pp. 517-531; Lawson, G.W., Belcher, R., Dawes, G.S., Redman, C.W., A comparison of ultrasound (with autocorrelation) and direct electrocardiogram fetal heart rate detector systems (1983) Am. J. Obstet. Gynecol., 147, pp. 721-722; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur. J. Obstet. Gynecol. Reprod. Biol., 114 (2), pp. 137-143; Lunghi, F., Magenes, G., Pedrinazzi, L., Signorini, M.G., Detection of fetal distress through a support vector machine based on fetal heart rate parameters (2005) Comput. Cardiol., 32, pp. 247-250; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000: Proc. IEEE-INNS-ENNS Int. Joint Conf. on Neural Networks, pp. 637-641; Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am. J. Obstet. Gynecol., 177 (6), pp. 1385-1390; Nijhuis, I., Ten Hof, J., Development of fetal heart rate and behavior: Indirect measures to assess the fetal nervous system (1999) Eur. J. Obstet. Gynecol. Reprod. Biol., 87 (1), pp. 1-2; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin. Obstet. Gynaecol., 8, pp. 643-661; Peters, C.H., Ten Broeke, E.D., Andriessen, P., Vermeulen, B., Berendsen, R.C., Wijn, P.F., Oei, S.G., Beat-to-beat detection of fetal heart rate: Doppler ultrasound cardiotocography compared to direct ECG cardiotocography in time and frequency domain (2004) Physiol. Meas., 25 (2), pp. 585-593; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc. Natl. Acad. Sci. USA, 88, pp. 2297-2301; Pincus, S., Approximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Pincus, S., Viscarello, R., Approximate entropy: A regularity measure for fetal heart rate analysis (1992) Obstet. Gynecol., 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am. J. Physiol. Heart Circ. Physiol., 278, pp. 2039-H2049; Salamalekis, E., Thomopoulos, P., Giannaris, D., Salloum, I., Vasios, G., Prentza, A., Koutsouris, D., Computerised intrapartum diagnosis of fetal hypoxia based on fetal heart rate monitoring and fetal pulse oximetry recordings utilising wavelet analysis and neural networks (2002) BJOG, 109 (10), pp. 1137-1142; Signorini, M., Cerutti, S., Nonlinear properties of Cardiovascular Time Series (1999) Methodology and Clinical Applications of Blood Pressure and Heart Rate Analysis, pp. 73-89; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans. Biomed. Eng., 50 (3), pp. 365-373; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Uehara, S., Yajima, A., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am. J. Obstet. Gynecol., 182 (5), pp. 1227-1232; Heart rate variability. Standards of measurement, physiological interpretation, and clinical use (1996) Eur. Heart J., 17, pp. 354-381; Wilcox, M.A., Wang, W., Sahota, D.S., Dawkins, R.R., Chung, T.K., Chang, A.M., The effect of different sampling intervals on the measurement of intrapartum fetal heart rate variability (1997) Obstet. Gynecol., 89 (4), pp. 577-580; Yum, M.K., Kim, K., Kim, J.H., Park, E.Y., A consistent abnormality in the average local smoothness of fetal heart rate in growth-restricted fetuses affected by severe pre-eclampsia (2004) Hypertens. Res., 27 (12), pp. 911-918
Keywords: abdomen; Algorithms; article; Cardiotocography; commercial phenomena; Confidence interval; controlled study; correlation coefficient; delivery; Diagnosis, Computer-Assisted; Electrocardiography; electrode; entropy; External and internal monitoring; Female; fetus electrocardiography; fetus monitoring; Foetal heart rate (FHR); Frequency domain analysis; Heart; Heart rate; human; intermethod comparison; intrapartum care; Linear and nonlinear analysis; Linear Models; mathematical computing; Nonlinear Dynamics; normal human; priority journal; Reproducibility of Results; sensitivity and specificity; sensor; Signal Processing, Computer-Assisted; Statistical significance; ultrasound; Variability

Leptin effect on RANKL and OPG expression in MC3T3-E1 osteoblasts - Lamghari, M.; Tavares, L.; Camboa, N.; Barbosa, M.A. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2006)
Recent studies have suggested that leptin hormone may play a pivotal role on bone remodeling through a direct effect by modulating positively the OPG/RANKL balance. Here, we investigate the effect of leptin hormone on RANKL and OPG expression in MC3T3-E1 osteoblasts using RT-PCR and ELISA measurements. We have at first identified the expression of Ob-Rb and Ob-Ra leptin receptor isoforms in MC3T3-E1 and observed that these cells respond to mrleptin treatments. We then investigated the effect of mrleptin on RANKL and OPG expression. We show that mrleptin dose-dependently regulated the expression of RANKL mRNA with complete inhibition observed at concentrations higher than 12 ng/ml. This effect was confirmed with sRANKL protein measurements. However, the exposure of MC3T3-E1 to mrleptin had no effect on OPG mRNA. Taken together, these results suggest that leptin modulates positively OPG/RANKL balance by inhibiting the expression of RANKL gene. © 2006 Wiley-Liss, Inc.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.20853PubMed ID: 16479591Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre 823, 4150-180, Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: osteoclast differentiation factor, 200145-93-3; osteoprotegerin, 205944-50-9; Alkaline Phosphatase, EC 3.1.3.1; Carrier Proteins; Glycoproteins; leptin receptor; Leptin; Membrane Glycoproteins; Osteoprotegerin; RANK Ligand; Receptor Activator of Nuclear Factor-kappa B; Receptors, Cell Surface; Receptors, Cytoplasmic and Nuclear; Receptors, Tumor Necrosis Factor; RNA, Messenger; Tnfrsf11a protein, mouse; Tnfrsf11b protein, mouse; Tnfsf11 protein, mouseReferences: Burguera, B., Hofbauer, L.C., Thomas, T., Gori, F., Evans, G.L., Khosla, S., Riggs, B.L., Turner, R.T., Leptin reduces ovariectomy-induced bone loss in rats (2001) Endocrinology, 142, pp. 3546-3553;Cornish, J., Callon, K.E., Bava, U., Lin, C., Naot, D., Hill, B.L., Grey, A.B., Reid, I.R., Leptin directly regulates bone cell function in vitro and reduces bone fragility in vivo (2002) J Endocrinol, 175, pp. 405-415; Ducy, P., Amling, M., Takeda, S., Priemel, M., Schilling, A.F., Beil, F.T., Shen, J., Karsenty, G., Leptin inhibits bone formation through a hypothalamic relay: A central control of bone mass (2000) Cell, 100, pp. 197-207; Elefteriou, F., Ahn, J.D., Takeda, S., Starbuck, M., Yang, X., Liu, X., Kondo, H., Karsenty, G., Leptin regulation of bone resorption by the sympathetic nervous system and CART (2005) Nature, 434, pp. 514-520; Elmquist, J.K., Hypothalamic pathways underlying the endocrine, autonomic, and behavioral effects of leptin (2001) Physiol Behav, 74, pp. 703-708; Gordeladze, J.O., Drevon, C.A., Syversen, U., Reseland, J.E., Leptin stimulates human osteoblastic cell proliferation, de novo collagen synthesis, and mineralization: Impact on differentiation markers, apoptosis, and osteoclastic signaling (2002) J Cell Biochem, 85, pp. 825-836; Holloway, W.R., Collier, F.M., Aitken, C.J., Myers, D.E., Hodge, J.M., Malakellis, M., Gough, T.J., Nicholson, G.C., Leptin inhibits osteoclast generation (2002) J Bone Miner Res, 17, pp. 200-209; Horwood, N.J., Elliott, J., Martin, T.J., Gillespie, M.T., Osteotropic agents regulate the expression of osteoclast differentiation factor and osteoprotegerin in osteoblastic stromal cells (1998) Endocrinology, 139, pp. 4743-4746; Kanematsu, M., Yoshimura, K., Takaoki, M., Sato, A., Vector-averaged gravity regulates gene expression of receptor activator of NF-κB (RANK) ligand and osteoprotegerin in bone marrow stromal cells via cyclic AMP/protein kinase A pathway (2002) Bone, 30, pp. 553-558; Lacely, D.L., Timms, E., Tan, H.L., Dunstan, C.R., Burgess, T., Elliott, R., Colombero, A., Boyle, W.J., Osteoproteferin ligand is a cytokine that regulates osteoclast differentiation and activation (1998) Cell, 93, pp. 165-167; Lee, S.K., Lorenzo, J.A., Parathyroid hormone stimulates TRANCE and inhibits osteoprotegerin messenger ribonucleic acid expression in murine bone marrow cultures: Correlation with osteoclast-like cell formation (1999) Endocrinology, 140, pp. 3552-3561; Lee, S.K., Lorenzo, J.A., Regulation of receptor activator of nuclear factor-κB ligand and osteoprotegerin mRNA expression by parathyroid hormone is predominantly mediated by the protein kinase a pathway in murine bone marrow cultures (2002) Bone, 31, pp. 252-259; Lee, Y.J., Park, J.H., Ju, S.K., You, K.H., Ko, J.S., Kim, H.M., Leptin receptor isoform expression in rat osteoblasts and their functional analysis (2002) FEBS Lett, 528, pp. 43-47; Liu, J., Yang, H., Liu, W., Cao, X., Feng, X., Sp1 and Sp3 regulate the basal transcription of receptor activator of nuclear factor kappa B ligand gene in osteoblasts and bone marrow stromal cells (2005) J Cell Biochem, 96 (4), pp. 716-727; Martin, A., De Vittoris, R., David, V., Moraes, R., Bégeot, M., Lafage-Proust, M.H., Alexandre, C., Thomas, T., Leptin modulates both résorption and formation while preventing disuse-induced bone loss in tail-suspended female rats (2005) Endocrinology, 146, pp. 3652-3659; Nagai, M., Sato, N., Reciprocal gene expression of osteoclastogenesis inhibitory factor and osteoclast differentiation factor regulates osteoclast formation (1999) Biochem Biophys Res Commun, 257, pp. 719-723; Nakajima, R., Inada, H., Koike, T., Yamano, T., Effects of leptin to cultured growth plate chondrocytes (2003) Horm Res, 60 (2), pp. 91-98; Parhami, F., Tintut, Y., Ballard, A., Fogelman, A.M., Demer, L.L., Leptin enhances the calcification of vascular cells: Artery wall as a target of leptin (2001) Circ Res, 88 (9), pp. 954-960; Reseland, J.E., Syversen, U., Bakke, I., Ovigstad, G., Eide, L.G., Hjertner, O., Gordeladze, J.O., Drevon, C.A., Leptin is expressed in and secreted from primary cultures of human osteoblasts and promotes bone mineralization (2001) J Bone Miner Res, 16, pp. 1426-11414; Rubin, J., Ackert-Bicknell, C., Zhu, L., Fan, X., Murphy, T., Nanes, M., Marcus, R., Rosen, C., Insulin like growth factor-I (IGF-I) regulates osteoprotegerin (OPG) and RANK ligand (RANKL) in vitro and osteoprotogerin in vivo (2002) J Clin Endocrinal Metab, 87, pp. 4273-4279; Rubin, J., Murphy, T., Fan, X., Goldschmidt, M., Taylor, W., Mechanical strain inhibits RANKL expression through activation of ERK1/2 in bone marrow stromal cells (2002) J Bone Miner Res, 17, pp. 1452-1460; Simonet, W.S., Lacey, D.L., Dunstan, C.R., Kelley, M., Chang, M.S., Luthy, R., Nguyen, H.Q., Boyle, W.J., Osteoprotegerin: A novel secreted protein involved in the regulation of bone density (1997) Cell, 89, pp. 309-319; Steppan, C.M., Crawford, T., Chidsey-Frink, K.L., Ke, H.Z., Swick, A.G., Leptin is a potent stimulator of bone growth in ob/ob mice (2000) Regul Pept, 92, pp. 73-78; Suda, T., Ueno, Y., Fujii, K., Shinki, T., Vitamin D and bone (2003) J Cell Biochem, 88, pp. 259-266; Thomas, T., Gori, F., Khosla, S., Jensen, M.D., Burguera, B., Riggs, B.L., Leptin acts on human marrow stromal cells to enhance differentiation to osteoblasts and to inhibit differentiation to adipocytes (1999) Endocrinology, 140, pp. 1630-1638; Udagawa, N., Takahashi, N., Yasuda, H., Mizuno, A., Itoh, K., Ueno, Y., Shinki, T., Suda, T., Osteoprotegerin produced by osteoblasts is an important regulator in osteoclast development and function (2000) Endocrinology, 141, pp. 3478-3484; Wamoto, I., Fujino, T., Douchi, T., The leptin receptor in human osteoblasts and the direct effect of leptin on bone metabolism (2004) Gynecol Endocrinol, 19, pp. 97-104; Yasuda, H., Shima, N., Nakagawa, N., Yamaguchi, K., Kinosaki, M., Mochizuki, S., Tomoyasu, A., Suda, T., Osteoclast differentiation factor is a ligand for osteoprotegerin/ osteoclastogenesis-inhibitory factor and is identical to TRANCE/RANKL (1998) Proc Natl Acad Sci USA, 95, pp. 3597-3602
Keywords: alkaline phosphatase; animal cell; Animals; article; bone remodeling; Carrier Proteins; Cell Line; enzyme linked immunosorbent assay; gene expression; gene expression regulation; Glycoproteins; hormone action; leptin; leptin receptor; leptin receptor a; leptin receptor b; MC3T3-E1; Membrane Glycoproteins; messenger RNA; Mice; mouse; nonhuman; Ob-Ra; Ob-Rb; OPG; osteoblast; Osteoblasts; osteoclast differentiation factor; Osteoprotegerin; priority journal; protein expression; RANK Ligand; RANKL; Receptor Activator of Nuclear Factor-kappa B; Receptors, Cell Surface; Receptors, Cytoplasmic and Nuclear; Receptors, Tumor Necrosis Factor; reverse transcription polymerase chain reaction; RNA extraction; RNA, Messenger; unclassified drug

Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bernardes, J. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 2006)
Linear and nonlinear fetal heart rate (FHR) indices, namely mean FHR, interval index (II), very low, low and high frequencies, approximate (ApEn) and sample entropy (SampEn), were computed, immediately before delivery, in the initial and final FHR tracing segments, from 48 normal, 10 mildly acidemic and 10 moderate-to-severely acidemic fetuses. Progression of labor was associated with a significant increase in linear frequency domain indices whereas nonlinear indices were significantly decreased. Moderate-to-severe fetal acidemia was associated with a significant decrease in nonlinear indices. The best discrimination between moderate-to-severe acidemic fetuses and the remaining cases was obtained combining II and ApEn(2,0.15), with a specificity of 71% and a sensitivity of 80%. These findings support the hypothesis of increased autonomic nervous system activity in the final minutes of labor and of decreased central nervous system activity, both in the final minutes of labor and in moderate-to-severe acidemic fetuses. © International Federation for Medical and Biological Engineering 2006.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: MBECDdoi: 10.1007/s11517-006-0105-6PubMed ID: 16988896Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade do Porto, Rua do Campo Alegre - 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptChemicals/CAS: AcidsReferences: ACOG technical bulletin. Fetal heart rate patterns: Monitoring, interpretation, and management (1995) Int J Gynecol Obstet, 51, pp. 65-74. , ACOG;Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynecol, 106, pp. 1307-1310; Ayres-de-Campos, D., Bernardes, J., Garrido, A., de Sá, J.M., Pereira-Leite, L., Sisporto 2.0: A program for automated analysis of cardiotocograms (2000) J Mat Fet Med, 9, pp. 311-318; Bernardes, J., de Campos, D.A., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynecol Obstet, 62, pp. 141-147; Bernardes, J., Costa-Pereira, A., de Campos, D.A., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57 (1), pp. 33-37; Bernardes, J., Moura, C., de Sá, J.P.M., Pereira-Leite, L., The porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Boog, G., Analyse informatisTe du rythme cardiaque foetal au cours de la grossesse et de l'accouchement (2004) EncyclopTdie MTdico-Chirurgicale, 148, pp. 1-10. , (5-049-D-23); Carter, M.C., Signal processing and display - Cardiotocographs (1993) Br J Obstet Gynaecol, 100 (9), pp. 21-23; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J Matern Fetal Invest, 8, pp. 23-26; Chung, D.Y., Sim, Y.B., Park, K.T., Yi, S.H., Shin, J.C., Kim, S.P., Spectral analysis of fetal heart rate variability as a predictor of intrapartum fetal distress (2001) Int J Gynecol Obstet, 73, pp. 109-116; Colenbrander, G.J., van Geijn, H.P., Goovaerts, H.G., Acquisition of fetal heart rate signals (1994) A Critical Appraisal of Fetal Surveillance, pp. 203-210. , In: Geijn HPV, Copray FJA (eds) Elsevier Science, Amsterdam; Dawes, G.S., Moulden, M., Sheil, O., Redman, C.W.G., Approximate entropy, a statistic of regularity, applied to fetal heart rate data before and during labour (1992) Obstet Gynecol, 80 (5), pp. 763-768; Dudewicz, E., Mishra, S., (1988) Modern Mathematical Statistics, , Wiley, New York; Echeverrfa, J.C., Hayes-Gill, B.R., Crowe, J.A., Woolfson, M.S., Croaker, G.D.H., Detrended fluctuation analysis: A suitable method for studying fetal heart rate variability? (1990) Int J Biomed Comput, 25, pp. 287-294; Felgueiras, C., de Sá, J.P.M., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed Eng, 36 (2), pp. 197-201; Fusheng, Y., Bo, H., Qingyu, T., Approximate entropy and its application in biosignal analysis (1998) Nonlinear Biomedical Signal Processing. Dynamical Analysis and Modelling, 2, pp. 72-91. , In: Akay M (ed) IEEE Press, New York; Gonçalves, H., Rocha, A.P., de Campos, D.A., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Gough, N.A., Fractal analysis of foetal heart rate variability (1993) Physiol Meas, 14 (3), pp. 309-315; Hayes, M., (1996) Statistical Digital Signal Processing and Modelling, , Wiley, New York; Hewlett-Packard, (1993) Hewlett-Packard Series 50 Service Manual, , M1351A and 1353A. Germany; King, T., Parer, J., The physiology of fetal heart rate patterns and perinatal asphyxia (2000) J Perinat Neonat Nurs, 14 (3), pp. 19-39; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur J Obstet Gynecol Reprod Biol, 114, pp. 137-143; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks,, 3, pp. 637-641. , In: IJCNN 2000; Martin, J.C.B., Electronic fetal monitoring: A brief summary of its development, problems and prospects (1998) Eur J Obstet Gynecol Reprod Biol, 78, pp. 133-140; Martinez, W.L., Martinez, A.R., (2002) Computational Statistics Handbook With MATLAB, , CRC Press, Boca Raton; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin Obstet Gynaecol, 8 (3), pp. 643-661; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci USA, 88, pp. 2297-2301; Pincus, S., Approximate entropy (apen) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Pincus, S., Viscarello, R., Approximate entropy: A regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79 (2), pp. 249-255; di Renzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Indraccolo, R., Cosmi, E.V., Fractal analysis: A new method for evaluating fetal heart rate variability (1996) J Perinat Med, 24 (3), pp. 261-269; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Ripley, B.D., (1996) Pattern Recognition and Neural Networks, , Cambridge University Press, London; Rooth, G., Huch, A., Huch, R., FIGO news. Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, p. 159; (2001) Evidence-Based Clinical Guideline Number 8. The Use of Electronic Fetal Monitoring, , Royal College of Obstetricians and Gynaecologists Royal College of Obstetricians and Gynaecologists, London; Salamalekis, E., Thomopoulos, P., Giannaris, D., Salloum, I., Vasios, G., Prentza, A., Koutsouris, D., Computerised intrapartum diagnosis of fetal hypoxia based on fetal heart rate monitoring and fetal pulse oximetry recordings utilising wavelet analysis and neural networks (2002) BJOG, 109 (10), pp. 1137-1142; Signorini, M.G., Cerutti, S., Nonlinear properties of cardiovascular time series (1999) Methodology and Clinical Applications of Blood Pressure and Heart Rate Analysis, pp. 73-89. , In: Di Rienzo M, Mancia G, Parati G, Pedotti A, Zanchetti A (eds) IOS Press, Amsterdam; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50 (3), pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Valimaki, I.A., Rosen, K.G., Ekholm, E.M., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labour (2005) Br J Obstet Gynaecol, 112, pp. 418-423; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Murotsuki, N.Y.J., Uehara, S., Yajima, A., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232; Heart rate variability. Standards of measurement, physiological interpretation, and clinical use. Task force of the european society of cardiology and the north american society of pacing and electrophysiology (1996) Eur Heart J, 17, pp. 354-381. , Task-Force; Teich, M.C., Lowen, S.B., Jost, B.M., Vibe-Rheymer, K., Heneghan, C., Heart rate variability: Measures and models (1998) Nonlinear Biomedical Signal Processing. Dynamic Analysis and Modeling, 2, pp. 159-213. , In: Akay M (ed) IEEE Press, New York; Yum, M.K., Kim, K., Kim, J.H., Park, E.Y., A consistent abnormality in the average local smoothness of fetal heart rate in growth-restricted fetuses affected by severe pre-eclampsia (2004) Hypertens Res, 27 (12), pp. 911-918
Keywords: acidemia; Acidosis; Acids; article; autonomic nervous system; Biological materials; Cardiology; Central nervous system; clinical article; controlled study; delivery; Delivery, Obstetric; Discriminant Analysis; disease severity; entropy; Fetal Diseases; Fetal heart rate; Fetal heart rate (FHR); Fetal monitoring; fetus; fetus heart rate; Frequency domain analysis; Heart Rate, Fetal; human; Humans; hypothesis; labor; Linear and nonlinear indices; linear system; Neurology; newborn; nonlinear system; Prenatal Care; Second stage of labor; sensitivity and specificity; Severity of Illness Index

Lung parenchyma segmentation from CT images based on material decomposition - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
We present a fully automated method for extracting the lung region from volumetric X-ray CT images based on material decomposition. By modeling the human thorax as a composition of different materials, the proposed method follows a threshold-based, hierarchical voxel classification strategy. The segmentation procedure involves the automatic computation of threshold values and consists on three main steps: patient segmentation and decomposition, large airways extraction and lung parenchyma decomposition, and lung region of interest segmentation. Experimental results were performed on thoracic CT images acquired from 30 patients. The method provides a reproducible set of thresholds for accurate extraction of the lung parenchyma, needed for computer aided diagnosis systems. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68310Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Vinhais, C.; Instituto de Engenharia Biomédica, Laboratório de Sinal e Imagem Biomédica, Campus da FEUP, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: cav@isep.ipp.ptReferences: Armato, S.G., Giger, M.L., Moran, C.J., Doi, K., MacMahon, H., Computerized detection of lung nodules in computed tomography scans (1998) Proceedings of the 1st International Workshop on Computer-aided Diagnosis, pp. 119-124;Armato III, S.G., Giger, M.L., Morgan, C.J., Blackburn, J.T., Doi, K., MacMahon, H., Computerized detection of pulmonary nodules on CT scans (1999) RadioGraphics, 19 (5), pp. 1303-1311; Brown, M.S., McNitt-Gray, M.F., Goldin, J.G., Suh, R.D., Sayre, J.W., Aberle, D.R., Patient-specific models for lung nodule detection and surveillance in CT images (2001) IEEE Trans. on Medical Imaging, 20 (12), pp. 1242-1250; Gurcan, M.N., Sahiner, B., Petrick, N., Chan, H.-P., Kazerooni, E.A., Cascade, P.N., Hadjiiski, L., Lung nodule detection on thoracic computed tomography images: Preliminary evaluation of a computer-aided diagnosis system (2002) Medical Physics, 29 (11), pp. 2552-2558; Armato III, S.G., Sensakovic, W.F., Automated lung segmentation for thoracic CT: Impact on computer-aided diagnosis (2004) Academic Radiology, 11, pp. 1011-1021; Kemerink, G.J., Lamers, R.J.S., Pellis, B.J., Kruize, H.H., Van Engelshoven, J.M.A., On segmentation of lung parenchyma in quantitative computed tomography of the lung (1998) Medical Physics, 25 (12), pp. 2432-2439; Brown, M.S., McNitt-Gray, M.F., Goldin, J.G., Greaser, L.E., Aberle, D.R., Knowledge-based method for segmentation and quantitative analysis of lung function from CT (1998) Proceedings of the 1st International Workshop on Computer-aided Diagnosis, pp. 113-118; Leader, J.K., Zheng, B., Rogers, R.M., Sciurba, F.C., Perez, A., Chapman, B.E., Patel, S., Gur, D., Automated lung segmentation in X-ray computed tomography: Development and evaluation of a heuristic threshold-based scheme (2003) Academic Radiology, 10, pp. 1224-1236; Hu, S., Hoffman, E.A., Reinhardt, J.M., Automatic lung segmentation for accurate quantitation of volumetric X-ray CT images (2001) IEEE Trans. on Medical Imaging, 20 (6), pp. 490-498; Alvarez, R.E., Macovsky, A., Energy-selective reconstruction in X-ray computerized tomography (1976) Phys. Med. Biol., 21, pp. 733-744; Lehmann, L.A., Alvarez, R.E., Macovski, A., Brody, W.R., Generalized image combinations in dual KVP digital radiography (1981) Medical Physics, 8 (5), pp. 659-667; Macovsky, A., (1983) Medical Imaging Systems, , Information and Systems Science Series, Prentice Hall, Inc; Tissue substitutes in radiation dosimetry and measurement (1989) Report 44 of the International Commission on Radiation Units and Measurements, , Bethesda, MD; Berger, M.J., Hubbell, J.H., XCOM: Photon cross sections on a personal computer (1987) NBSIR, 87 (3597); Boone, J.M., Seibert, J.A., An accurate method for computer-generating tungsten anode x-ray spectra from 30 to 140 kV (1997) Medical Physics, 24 (11), pp. 1661-1670; Rijsbergen, C.J.V., (1979) Information Retrieval, , London, Butterworths, 2nd ed
Keywords: Biological organs; Classification (of information); Computer simulation; Computerized tomography; Image segmentation; Lung parenchyma; Medical imaging; Patient segmentation; Patient treatment; Volumetric X-ray CT images; Voxel classification strategy

A model for educational simulation of neonatal cardiovascular pathophysiology. - Sá Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in healthcare : journal of the Society for Simulation in HealthcareSimul Healthc, 2006)
Full-body patient simulators provide a technological basis for clinical education without risk to real patients. In a previous study, we described a model for educational simulation of infant cardiovascular physiology. Using essentially the same methodology, we derive a mathematical model for the cardiovascular system of a healthy 1-week-old neonate. Computer simulations of this model result in vital signs that are close to target hemodynamic variables. Simulated systemic arterial pressure waveform and left ventricular pressure-volume loop are realistic, and the system reacts appropriately to blood loss. We also adapt the model structure and change its parameters to reflect the congenital heart defects: patent ductus arteriosus, tetralogy of Fallot, complex coarctation of the aorta with patent foramen ovale, and transposition of the great arteries. Simulated vital signs are again close to target hemodynamic variables. The resulting model for neonatal cardiovascular pathophysiology is an essential step in attaining a full-body, model-driven neonatal acute care simulator.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusPubMed ID: 19088566Language of Original Document: EnglishCorrespondence Address: Sá Couto, C.D.
Keywords: article; cardiovascular disease; Cardiovascular Diseases; cardiovascular function; Cardiovascular Physiological Phenomena; cardiovascular system; Computer simulation; congenital heart malformation; Education, Medical, Graduate; educational model; Heart Defects, Congenital; human; Humans; infant welfare; Infant, Newborn; medical education; methodology; Models, Educational; Models, Theoretical; newborn; theoretical model

Modular neural network task decomposition via entropic clustering - Santos, J.M.; Alexandre, L.A.; De Sá, J.M. (Proceedings - ISDA 2006: Sixth International Conference on Intelligent Systems Design and ApplicationsProc. ISDA Sixth Int. Conf. Intelligent Syst. Design Applic., 2006)
The use of monolithic neural networks (such as a multilayer perceptron) has some drawbacks: e.g. slow learning, weight coupling, the black box effect. These can be alleviated by the use of a modular neural network. The creation of a MNN has three steps: task decomposition, module creation and decision integration. In this paper we propose the use of an entropie clustering algorithm as a way of performing task decomposition. We present experiments on several real world classification problems that show the performance of this approach. © 2006 IEEE.
Conference code: 69992Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 4021410doi: 10.1109/ISDA.2006.198Language of Original Document: EnglishCorrespondence Address: Santos, J.M.; Instituto Superior de Engenharia do Porto, Instituto de Engenharia Biomédica, Porto, Portugal; email: jms@isep.ipp.ptReferences: Santos, J.M., Marques de Sá, J., Alexandre, L.A., LEGClust - a clustering algorithm based on layered entropie subgraphs (2005) IEEE Transactions on Pattern Analysis and Machine Intelligence, , submitted;Bauer, E., Kohavi, R., An empirical comparison of voting classification algorithms: Bagging, boosting, and variants (1999) Machine Learning, 36 (1-2), pp. 105-139; Dietterich, T.G., An experimental comparison of three methods for constructing ensembles of decision trees: Bagging, boosting, and randomization (2000) Machine Learning, 40 (2), pp. 139-157; Kittler, J., Hatef, M., Duin, R.P.W., Matas, J., On combining classifiers (1998) IEEE Trans. Pattern Anal. Mach. Intell, 20 (3), pp. 226-239; Allwein, E.L., Schapire, R.E., Singer, Y., Reducing multiclass to binary: A unifying approach for margin classifiers (2000) Proc. 17th International Conf on Machine Learning, pp. 9-16. , Morgan Kaufmann, San Francisco, CA; Alexandre, L.A., Campilho, A.C., Kamel, M., Bounds for the average generalization error of the mixture of experts neural network (2004) LNCS, 3138, pp. 618-625. , 5th International Workshop on Statistical Techniques in Pattern Recognition; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Auda, G., Kamel, M., Modular neural network classifiers: A comparative study (1998) Intel. Robotic Systems, 21, pp. 117-129; Jordan, M., Jacobs, R., Hierarchical mixture of experts and the EM algorithm (1994) Neural Computation, 6, pp. 181-214; Jacobs, R., Peng, F., Tanner, M., A bayesian approach to model selection in hierarchical mixtures-of-experts architectures (1997) Neural Networks, 10 (2), pp. 231-241; Vilalta, R., Achari, M.K., Eick, C.F., Class decomposition via clustering: A new framework for lowvariance classifiers (2003) Third IEEE International Conference on Data Mining, pp. 673-676; Alexandre, L.A., Campilho, A.C., Kamel, M., A probabilistic model for the cooperative modular neural network (2003) LNCS, 2652, pp. 11-18. , Proceedings of the IbPRIA 2003; Ennaji, A., Ribert, A., Lecourtier, Y., From data topology to a modular classifier (2003) International Journal on Document Analysis and Recognition, 6 (1), pp. 1-9; Ng, A.Y., Jordan, M.I., Weiss, Y., On spectral clustering: Analysis and an algorithm (2001) Advances in Neural Information Processing Systems, 14; Bowman, A.W., Azzalini, A., (1997) Applied Smooting Techniques for Data Analysis, , London:Oxford University Press; Marques de Sá, J., (2003) Applied statistics using SPSS, STATISTICA andMATLAB, , Springer; Blake, C., Keogh, E., Merz, C., (1998) UCI repository of machine learning databases; Forina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of Italian olive oils (1981) Ann. Chim. (Rome), 72, pp. 127-155
Keywords: Classification (of information); Clustering algorithms; Decision Theory; Entropic clustering; Learning systems; Modular neural network task decomposition; Monolithic neural networks; Neural networks; Weight coupling

A multiclassifier approach for lung nodule classification - Pereira, C.S.; Alexandre, L.A.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
The aim of this paper is to examine a multiclassifier approach to the classification of the lung nodules in X-ray chest radiographs. The approach investigated here is based on an image region-based classification whose output is the information of the presence or absence of a nodule in an image region. The classification was made, essentially, in two steps: firstly, a set of rotation invariant features was extracted from the responses of a multi-scale and multi-orientation filter bank; secondly, different classifiers (multi-layer perceptrons) are designed using different features sets and trained in different data. These classifiers are further combined in order to improve the classification performance. The obtained results are promising and can be used for reducing the false-positives nodules detected in a computer-aided diagnosis system. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68310Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pereira, C.S.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: cpereira@estgl.ipv.ptReferences: Jemal, A., Murray, T., Ward, E., Samuels, A., Tiwari, R.C., Ghafoor, A., Feuer, E.J., Thun, M.J., (2005) Cancer Statistics, 2005, 55, pp. 10-30. , CA Cancer J Clin;Keserci, B., Yoshida, H., Computerized detection of pulmonary nodules in chest radiographs based on morphological features and wavelet snake model (2002) Medical Image Analysis, 6, pp. 431-447; Van Ginneken, B., Romeny, B.M.H., Viergever, M.A., Computer-aided diagnosis in chest radiography: A survey (2001) IEEE Transactions on Medical Imaging, 20 (12), pp. 1228-1241; Wei, J., Hagihara, Y., Shimizu, A., Kobatake, H., Optimal image feature set for detecting lung nodules on chest X-ray images (2002) CARS 2002; Van Ginneken, B., Katsuragawa, S., Ter Haar Romeny, B.M., Kunio, D., Viergever, M.A., Automatic detection of abnormalities in chest radiographs using local texture analysis (2002) IEEE Transactions on Medical Imaging, 21, pp. 139-149; Schilham, A.M.R., Van Ginneken, B., Loog, M., Multi-scale nodule detection in chest radiographs (2003) Lecture Notes in Computer Science, LNCS 2878, pp. 602-609; Shiraishi, J., Katsuragawa, S., Ikezoe, J., Matsumoto, T., Kobayashi, T., Matsu, K.-I.K., Matsui, M., Doi, K., Development of a digital image database for chest radiographs with and without a lung nodule: Receiver operating characteristic analysis of radiologists' detection of pulmonary nodules (2000) American Journal of Roentgenology, 174, pp. 71-74; Yoshida, H., Local contralateral subtraction based on bilateral symmetry of lung for reduction of false positives in computerized detection of pulmonary nodules (2004) IEEE Transactions on Biomedical Engineering, 51, pp. 778-789; Suzuki, K., Shiraishi, J., Abe, H., MacMahon, H., Doi, K., False-positive reduction in computer-aided diagnostic scheme for detecting nodules in chest radiographs by means of massive training artificial neural network (2005) Academic Radiology, 12, pp. 191-201; Randen, T., Husoy, J.H., Filtering for texture classification: A comparative study (1999) IEEE Transactions on Pattern Analysis and Machine Intelligence, 21 (4); Grigorescu, S.E., Petkov, N., Kruizinga, P., Comparison of texture features based on Gabor filters (2002) IEEE Transactions on Image Processing, 11 (10), pp. 195-203; Kumar, A., Pang, G.K.H., Defect detection in textured materials using Gabor filters (2002) IEEE Transactions on Industry Applications, 38 (2); Varma, M., Zisserman, A., Unifying statistical texture classification frameworks (2004) Image and Vision Computing, 22, pp. 1175-1183; Leung, T., Malik, J., Representing and recognizing the visual appearance of materials using three-dimensional textons (2001) International Journal of Computer Vision, 43, pp. 29-44; Alexandre, L.A., Campilho, A.C., Kamel, M., On combining classifiers using sum and product rules (2001) Pattern Recognition Letters, 22, pp. 1283-1289
Keywords: Biological organs; Classification (of information); Computer aided diagnosis; False-positives nodules; Medical imaging; Multi-orientation filter bank; Radiography; X rays; X-ray chest radiographs

New developments of the Z-EDM algorithm - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Proceedings - ISDA 2006: Sixth International Conference on Intelligent Systems Design and ApplicationsProc. ISDA Sixth Int. Conf. Intelligent Syst. Design Applic., 2006)
In this paper we address some open questions on the recently proposed Zero-Error Density Maximization algorithm for MLP training. We propose a new version of the cost function that solves a training problem encountered in previous work and prove that the use of a nonparametric density estimator preserves the optimal solution. Some experiments are reported comparing this cost function to the usual mean-square error and cross entropy cost junctions. © 2006 IEEE.
Conference code: 69992Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusArt. No.: 4021587doi: 10.1109/ISDA.2006.204Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; INEB - Instituto de Engenharia Biomédica, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Bishop, C., (1995) Neural Networks for Pattern Recognition, , Oxford University Press;Blake, C., Merz, C., (1998) UCI Repository of machine learning databases University of California, , http://www.ics.uci.edu/~mlearn/MLRepository.html, Irvine, Dept. of Information and Computer Sciences; Erdogmus, D., Principe, J.C., An Error-Entropy Minimization Algorithm for Supervised Training of Nonlinear Adaptive Systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Forina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of Italian olive oils (1981) Ann. Chim. (Rome), 50, pp. 127-155; Marques de Sá, J., (2001) Pattern Recognition: Concepts, Methods and Applications, , Springer Verlag; J. Santos, L. Alexandre, and J. Marques de Sá. The Error Entropy Minimization Algorithm for Neural Network Classification. In Int. Conf. on Recent Advances in Soft Computing, Nottingham, United Kingdom, 2004Silva, L., Alexandre, L., Marques de Sá, J., Neural network classification: Maximizing zero-error density (2005) LNCS, 3686, pp. 127-135. , ICAPR 2005; Silva, L., Marques de Sá, J., Alexandre, L., Neural Network Classification using Shannon's Entropy (2005) European Symposium on Artificial Neural Networks; Silverman, B., (1986) Density Estimation for Statistics and Data Analysis, , Chapman & Hall
Keywords: Algorithms; Cost functions; Mean square error; MLP training; Nonparametric density estimators; Optimization; Personnel training; Problem solving; Zero-Error Density Maximization algorithm

The N-terminal half of the peroxisomal cycling receptor Pex5p is a natively unfolded domain - Carvalho, A.F.; Costa-Rodrigues, J.; Correia, I.; Costa Pessoa, J.; Faria, T.Q.; Martins, C.L.; Fransen, M.; Sá-Miranda, C.; Azevedo, J.E. (Journal of Molecular BiologyJ. Mol. Biol., 2006)
Targeting of most newly synthesised peroxisomal matrix proteins to the organelle requires Pex5p, the so-called PTS1 receptor. According to current models of peroxisomal biogenesis, Pex5p interacts with these proteins in the cytosol, transports them to the peroxisomal membrane and catalyses their translocation across the membrane. Presently, our knowledge on the structural details behind the interaction of Pex5p with the cargo proteins is reasonably complete. In contrast, information regarding the structure of the Pex5p N-terminal half (a region containing its peroxisomal targeting domain) is still limited. We have recently observed that the Stokes radius of this Pex5p domain is anomalously large, suggesting that this portion of the protein is either a structured elongated domain or that it adopts a low compactness conformation. Here, we address this issue using a combination of biophysical and biochemical approaches. Our results indicate that the N-terminal half of Pex5p is best described as a natively unfolded pre-molten globule-like domain. The implications of these findings on the mechanism of protein import into the peroxisome are discussed. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JMOBAdoi: 10.1016/j.jmb.2005.12.002PubMed ID: 16403517Language of Original Document: EnglishCorrespondence Address: Azevedo, J.E.; Instituto de Biologia Molecular e Celular, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jazevedo@ibmc.up.ptChemicals/CAS: Amino Acids; peroxisome-targeting signal 1 receptor; Receptors, Cytoplasmic and NuclearReferences: Brown, L.A., Baker, A., Peroxisome biogenesis and the role of protein import (2003) J. Cell. Mol. Med., 7, pp. 388-400;Heiland, I., Erdmann, R., Biogenesis of peroxisomes. Topogenesis of the peroxisomal membrane and matrix proteins (2005) FEBS J., 272, pp. 2362-2372; Lazarow, P.B., Peroxisome biogenesis: Advances and conundrums (2003) Curr. Opin. Cell Biol., 15, pp. 489-497; Moyersoen, J., Choe, J., Fan, E., Hol, W.G., Michels, P.A., Biogenesis of peroxisomes and glycosomes: Trypanosomatid glycosome assembly is a promising new drug target (2004) FEMS Microbiol. Rev., 28, pp. 603-643; Weller, S., Gould, S.J., Valle, D., Peroxisome biogenesis disorders (2003) Annu. Rev. Genomics Hum. Genet., 4, pp. 165-211; Gould, S.J., Keller, G.A., Hosken, N., Wilkinson, J., Subramani, S., A conserved tripeptide sorts proteins to peroxisomes (1989) J. Cell Biol., 108, pp. 1657-1664; Klein, A.T., Barnett, P., Bottger, G., Konings, D., Tabak, H.F., Distel, B., Recognition of peroxisomal targeting signal type 1 by the import receptor Pex5p (2001) J. Biol. Chem., 276, pp. 15034-15041; Lametschwandtner, G., Brocard, C., Fransen, M., Van Veldhoven, P., Berger, J., Hartig, A., The difference in recognition of terminal tripeptides as peroxisomal targeting signal 1 between yeast and human is due to different affinities of their receptor Pex5p to the cognate signal and to residues adjacent to it (1998) J. Biol. Chem., 273, pp. 33635-33643; Brocard, C., Kragler, F., Simon, M.M., Schuster, T., Hartig, A., The tetratricopeptide repeat-domain of the PAS10 protein of Saccharomyces cerevisiae is essential for binding the peroxisomal targeting signal-SKL (1994) Biochem. Biophys. Res. Commun., 204, pp. 1016-1022; Dodt, G., Braverman, N., Wong, C., Moser, A., Moser, H.W., Watkins, P., Mutations in the PTS1 receptor gene, PXR1, define complementation group 2 of the peroxisome biogenesis disorders (1995) Nature Genet., 9, pp. 115-125; Fransen, M., Brees, C., Baumgart, E., Vanhooren, J.C., Baes, M., Mannaerts, G.P., Van Veldhoven, P.P., Identification and characterization of the putative human peroxisomal C-terminal targeting signal import receptor (1995) J. Biol. Chem., 270, pp. 7731-7736; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., A proposed model for the PEX5-peroxisomal targeting signal-1 recognition complex (2000) Proteins: Struct. Funct. Genet., 38, pp. 241-246; Otera, H., Setoguchi, K., Hamasaki, M., Kumashiro, T., Shimizu, N., Fujiki, Y., Peroxisomal targeting signal receptor Pex5p interacts with cargoes and import machinery components in a spatiotemporally differentiated manner: Conserved Pex5p WXXXF/Y motifs are critical for matrix protein import (2002) Mol. Cell. Biol., 22, pp. 1639-1655; Terlecky, S.R., Nuttley, W.M., McCollum, D., Sock, E., Subramani, S., The Pichia pastoris peroxisomal protein PAS8p is the receptor for the C-terminal tripeptide peroxisomal targeting signal (1995) EMBO J., 14, pp. 3627-3634; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., Peroxisomal targeting signal-1 recognition by the TPR domains of human PEX5 (2000) Nature Struct. Biol., 7, pp. 1091-1095; Agne, B., Meindl, N.M., Niederhoff, K., Einwachter, H., Rehling, P., Sickmann, A., Pex8p: An intraperoxisomal organizer of the peroxisomal import machinery (2003) Mol. Cell., 11, pp. 635-646; Albertini, M., Girzalsky, W., Veenhuis, M., Kunau, W.H., Pex12p of Saccharomyces cerevisiae is a component of a multi-protein complex essential for peroxisomal matrix protein import (2001) Eur. J. Cell Biol., 80, pp. 257-270; Reguenga, C., Oliveira, M.E., Gouveia, A.M., Sa-Miranda, C., Azevedo, J.E., Characterization of the mammalian peroxisomal import machinery: Pex2p. Pex5p, Pex12p, and Pex14p are subunits of the same protein assembly (2001) J. Biol. Chem., 276, pp. 29935-29942; Huhse, B., Rehling, P., Albertini, M., Blank, L., Meller, K., Kunau, W.-H., Pex17p of Saccharomyces cerevisiae is a novel peroxin and component of the peroxisomal protein translocation machinery (1998) J. Cell Biol., 140, pp. 49-60; Liu, H., Tan, X., Russell, K.A., Veenhuis, M., Cregg, J.M., PER3, a gene required for peroxisome biogenesis in Pichia pastoris, encodes a peroxisomal membrane protein involved in protein import (1995) J. Biol. Chem., 270, pp. 10940-10951; Rehling, P., Skaletz-Rorowski, A., Girzalsky, W., Voorn-Brouwer, T., Fransen, M.M., Distel, B., Pex8p, an intraperoxisomal peroxin of Saccharomyces cerevisiae required for protein transport into peroxisomes binds the PTS1 receptor pex5p (2000) J. Biol. Chem., 275, pp. 3593-3602; Smith, J.J., Szilard, R.K., Marelli, M., Rachubinski, R.A., The peroxin Pex17p of the yeast Yarrowia lipolytica is associated peripherally with the peroxisomal membrane and is required for the import of a subset of matrix proteins (1997) Mol. Cell. Biol., 17, pp. 2511-2520; Waterham, H.R., Titorenko, V.I., Haima, P., Cregg, J.M., Harder, W., Veenhuis, M., The Hansenula polymorpha PER1 gene is essential for peroxisome biogenesis and encodes a peroxisomal matrix protein with both carboxy- and amino-terminal targeting signals (1994) J. Cell Biol., 127, pp. 737-749; Costa-Rodrigues, J., Carvalho, A.F., Gouveia, A.M., Fransen, M., Sa-Miranda, C., Azevedo, J.E., The N terminus of the peroxisomal cycling receptor, Pex5p, is required for redirecting the peroxisome-associated peroxin back to the cytosol (2004) J. Biol. Chem., 279, pp. 46573-46579; Dodt, G., Gould, S.J., Multiple, P.E.X., Genes are required for proper subcellular distribution and stability of Pex5p, the PTS1 receptor: Evidence that PTS1 protein import is mediated by a cycling receptor (1996) J. Cell Biol., 135, pp. 1763-1774; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Reguenga, C., Sa-Miranda, C., Azevedo, J.E., Characterization of the peroxisomal cycling receptor, Pex5p, using a cell-free in vitro import system (2003) J. Biol. Chem., 278, pp. 226-232; Oliveira, M.E., Gouveia, A.M., Pinto, R.A., Sa-Miranda, C., Azevedo, J.E., The energetics of Pex5p-mediated peroxisomal protein import (2003) J. Biol. Chem., 278, pp. 39483-39488; Glover, J.R., Andrews, D.W., Rachubinski, R.A., Saccharomyces cerevisiae peroxisomal thiolase is imported as a dimer (1994) Proc. Natl Acad. Sci. USA, 91, pp. 10541-10545; McNew, J.A., Goodman, J.M., An oligomeric protein is imported into peroxisomes in vivo (1994) J. Cell Biol., 127, pp. 1245-1257; Stewart, M.Q., Esposito, R.D., Gowani, J., Goodman, J.M., Alcohol oxidase and dihydroxyacetone synthase, the abundant peroxisomal proteins of methylotrophic yeasts, assemble in different cellular compartments (2001) J. Cell Sci., 114, pp. 2863-2868; Walton, P.A., Hill, P.E., Subramani, S., Import of stably folded proteins into peroxisomes (1995) Mol. Biol. Cell, 6, pp. 675-683; Saidowsky, J., Dodt, G., Kirchberg, K., Wegner, A., Nastainczyk, W., Kunau, W.H., Schliebs, W., The di-aromatic pentapeptide repeats of the human peroxisome import receptor PEX5 are separate high affinity binding sites for the peroxisomal membrane protein PEX14 (2001) J. Biol. Chem., 276, pp. 34524-34529; Schliebs, W., Saidowsky, J., Agianian, B., Dodt, G., Herberg, F.W., Kunau, W.H., Recombinant human peroxisomal targeting signal receptor PEX5. Structural basis for interaction of PEX5 with PEX14 (1999) J. Biol. Chem., 274, pp. 5666-5673; Costa-Rodrigues, J., Carvalho, A.F., Fransen, M., Hambruch, E., Schliebs, W., Sa-Miranda, C., Azevedo, J.E., Pex5p, the peroxisomal cycling receptor, is a monomeric non-globular protein (2005) J. Biol. Chem., 280, pp. 24404-24411; Elgersma, Y., Elgersma-Hooisma, M., Wenzel, T., McCaffery, J.M., Farquhar, M.G., Subramani, S., A mobile PTS2 receptor for peroxisomal protein import in Pichia pastoris (1998) J. Cell Biol., 140, pp. 807-820; Rehling, P., Marzioch, M., Niesen, F., Wittke, E., Veenhuis, M., Kunau, W.H., The import receptor for the peroxisomal targeting signal 2 (PTS2) in Saccharomyces cerevisiae is encoded by the PAS7 gene (1996) EMBO J., 15, pp. 2901-2913; Zhang, J.W., Lazarow, P.B., Peb1p (Pas7p) is an intraperoxisomal receptor for the NH2-terminal, type 2, peroxisomal targeting sequence of thiolase: Peb1p itself is targeted to peroxisomes by an NH2-terminal peptide (1996) J. Cell Biol., 132, pp. 325-334; Dodt, G., Warren, D., Becker, E., Rehling, P., Gould, S.J., Domain mapping of human PEX5 reveals functional and structural similarities to Saccharomyces cerevisiae Pex18p and Pex21p (2001) J. Biol. Chem., 276, pp. 41769-41781; Einwachter, H., Sowinski, S., Kunau, W.H., Schliebs, W., Yarrowia lipolytica Pex20p Saccharomyces cerevisiae Pex18p/Pex21p and mammalian Pex5pL fulfil a common function in the early steps of the peroxisomal PTS2 import pathway (2001) EMBO Rep., 2, pp. 1035-1039; Matsumura, T., Otera, H., Fujiki, Y., Disruption of the interaction of the longer isoform of Pex5p, Pex5pL, with Pex7p abolishes peroxisome targeting signal type 2 protein import in mammals. Study with a novel Pex5-impaired Chinese hamster ovary cell mutant (2000) J. Biol. Chem., 275, pp. 21715-21721; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Insertion of Pex5p into the peroxisomal membrane is cargo protein-dependent (2003) J. Biol. Chem., 278, pp. 4389-4392; De La Torre, J.G., Hydrodynamics of segmentally flexible macromolecules (1994) Eur. Biophys. J., 23, pp. 307-322; Denning, D.P., Uversky, V., Patel, S.S., Fink, A.L., Rexach, M., The Saccharomyces cerevisiae nucleoporin Nup2p is a natively unfolded protein (2002) J. Biol. Chem., 277, pp. 33447-33455; Permyakov, S.E., Millett, I.S., Doniach, S., Permyakov, E.A., Uversky, V.N., Natively unfolded C-terminal domain of caldesmon remains substantially unstructured after the effective binding to calmodulin (2003) Proteins: Struct. Funct. Genet., 53, pp. 855-862; Uversky, V.N., Natively unfolded proteins: A point where biology waits for physics (2002) Protein Sci., 11, pp. 739-756; Lydakis-Simantiris, N., Hutchison, R.S., Betts, S.D., Barry, B.A., Yocum, C.F., Manganese stabilizing protein of photosystem II is a thermostable, natively unfolded polypeptide (1999) Biochemistry, 38, pp. 404-414; Sreerama, N., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Comparison of CONTIN, SELCON, and CDSSTR methods with an expanded reference set (2000) Anal. Biochem., 287, pp. 252-260; Stanley, W.A., Sokolova, A., Brown, A., Clarke, D.T., Wilmanns, M., Svergun, D.I., Synergistic use of synchrotron radiation techniques for biological samples in solution: A case study on protein-ligand recognition by the peroxisomal import receptor Pex5p (2004) J. Synchrotron Radiat., 11, pp. 490-496; Oberg, K.A., Fink, A.L., A new attenuated total reflectance Fourier transform infrared spectroscopy method for the study of proteins in solution (1998) Anal. Biochem., 256, pp. 92-106; Navea, S., Tauler, R., De Juan, A., Application of the local regression method interval partial least-squares to the elucidation of protein secondary structure (2005) Anal. Biochem., 336, pp. 231-242; Obradovic, Z., Peng, K., Vucetic, S., Radijovac, P., Dunker, A.K., Exploiting heterogeneous sequence properties improves prediction of protein disorder (2006) Proteins, , In the press; Gould, S.J., Collins, C.S., Opinion: Peroxisomal-protein import: Is it really that complex? (2002) Nature Rev. Mol. Cell. Biol., 3, pp. 382-389; Shoemaker, B.A., Portman, J.J., Wolynes, P.G., Speeding molecular recognition by using the folding funnel: The fly-casting mechanism (2000) Proc. Natl Acad. Sci. USA, 97, pp. 8868-8873; Pontius, B.W., Close encounters: Why unstructured, polymeric domains can increase rates of specific macromolecular association (1993) Trends Biochem. Sci., 18, pp. 181-186; Tompa, P., Intrinsically unstructured proteins (2002) Trends Biochem. Sci., 27, pp. 527-533; Gouveia, A.M., Reguenga, C., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Characterization of peroxisomal Pex5p from rat liver. Pex5p in the Pex5p-Pex14p membrane complex is a transmembrane protein (2000) J. Biol. Chem., 275, pp. 32444-32451; Dammai, V., Subramani, S., The human peroxisomal targeting signal receptor, Pex5p, is translocated into the peroxisomal matrix and recycled to the cytosol (2001) Cell, 105, pp. 187-196; Imanaka, T., Small, G.M., Lazarow, P.B., Translocation of acyl-CoA oxidase into peroxisomes requires ATP hydrolysis but not a membrane potential (1987) J. Cell Biol., 105, pp. 2915-2922; Wendland, M., Subramani, S., Cytosol-dependent peroxisomal protein import in a permeabilized cell system (1993) J. Cell Biol., 120, pp. 675-685; Azevedo, J.E., Costa-Rodrigues, J., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Protein translocation across the peroxisomal membrane (2004) Cell Biochem. Biophys., 41, pp. 451-468; Wang, D., Visser, N.V., Veenhuis, M., Van Der Klei, I.J., Physical interactions of the peroxisomal targeting signal 1 receptor pex5p, studied by fluorescence correlation spectroscopy (2003) J. Biol. Chem., 278, pp. 43340-43345; Oliveira, M.E., Reguenga, C., Gouveia, A.M., Guimaraes, C.P., Schliebs, W., Kunau, W.H., Mammalian Pex14p: Membrane topology and characterisation of the Pex14p-Pex14p interaction (2002) Biochim. Biophys. Acta, 1567, pp. 13-22; Fransen, M., Wylin, T., Brees, C., Mannaerts, G.P., Van Veldhoven, P.P., Human pex19p binds peroxisomal integral membrane proteins at regions distinct from their sorting sequences (2001) Mol. Cell. Biol., 21, pp. 4413-4424; Sreerama, N., Venyaminov, S.Y., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Inclusion of denatured proteins with native proteins in the analysis (2000) Anal. Biochem., 287, pp. 243-251; Vigano, C., Margolles, A., Van Veen, H.W., Konings, W.N., Ruysschaert, J.M., Secondary and tertiary structure changes of reconstituted LmrA induced by nucleotide binding or hydrolysis. a Fourier transform attenuated total reflection infrared spectroscopy and tryptophan fluorescence quenching analysis (2000) J. Biol. Chem., 275, pp. 10962-10967; Laurent, T.C., Killander, J., Theory of gel filtration + its experimental verification (1964) J. Chromatog., 14, pp. 217-230;
Keywords: Amino acids; amino terminal sequence; article; biogenesis; Calorimetry, Differential Scanning; cell membrane; cell receptor; Chromatography, Gel; circular dichroism; cytosol; differential scanning calorimetry; human; Humans; infrared spectroscopy; matrix protein; Natively unfolded; Peroxisomal protein import; peroxisome; Pex5p; priority journal; Protein conformation; protein degradation; protein domain; protein folding; protein interaction; protein Pex5p; protein structure; Protein Structure, Secondary; Protein Structure, Tertiary; protein transport; pts1 receptor; PTS1-receptor; Receptors, Cytoplasmic and Nuclear; Spectroscopy, Fourier Transform Infrared; unclassified drug

Osteoblast proliferation and morphology analysis on laser modified hydroxyapatite surfaces: Preliminary results - Teixeira, S.; Queiroz, A.C.; Monteiro, F.J.; Ferraz, M.P.; Vilar, R.; Eugénio, S. (Key Engineering MaterialsKey Eng Mat, 2006)
Biocompatibility has long been associated with surface microtopography, microtexture and microchemistry. The surface topography ultimately affects the nature and the strength of the interactions that occur at biomaterial-biological environment (cell adhesion, mobility, spreading and proliferation). Thus, it is necessary to produce and work with controlled microtopographical surfaces that present reproducible microdomains of a dimension similar to that of the biological elements of interest (for instance, cells). [1] There are a number of substrates that already have been studied (such as silicone, polystyrene, poly-L-lactic acid and titanium coated polystyrene) in terms of surface topography. [2] However, few studies are related to hydroxyapatite substrates. As it is well established, hydroxyapatite is a well known ceramic that is extremely used in medical applications, namely implants and coatings. In this work, the surface topography of dense hydroxyapatite substrates was altered by using KFr excimer laser. Excimer lasers produce high-intensity, pulsed ultraviolet radiation and are especially well suited for materials processing due to their large beam cross-section area, which permits using mask projection technologies to process relatively large areas in a single step.[3].
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Teixeira, S.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomaterlais, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: smsilva@ineb.up.ptReferences: Duncan, A.C., Laser microfabricated model surfaces for controlled cell growth (2002) Biosensors and Bioelectronics, 17, pp. 413-426;Walboomers, X.F., Contact guidance of rat fibroblasts on various implant materials (1999) Journal of Biomedical Materials Research, 47, pp. 204-212; Queiroz, A.C., Laser surface modifications of hydroxyapatite and glass-reinforced hydroxyapatite (2004) Biomaterials, 25, pp. 4607-4614; Ahmad, M., McCarthy, M.B., Gronowicz, G., An in vitro model for mineralization of human osteoblasts-like cells on implant materials (1999) Biomaterials, 20, pp. 211-220
Keywords: Bone; cell adhesion; Cells; Ceramic materials; Excimer laser; Excimer lasers; hydroxyapatite; Microtexture; Microtopography; morphology; Strength of materials; Surface modification; Surface topography; Surface treatment

Silicon addition to hydroxyapatite increases nanoscale electrostatic, van der Waals, and adhesive interactions - Vandiver, J.; Dean, D.; Patel, N.; Botelho, C.; Best, S.; Santos, J.D.; Lopes, M.A.; Bonfield, W.; Ortiz, C. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The normal intersurface forces between nanosized probe tips functionalized with COO
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30737PubMed ID: 16646067Language of Original Document: EnglishCorrespondence Address: Ortiz, C.; Department of Materials Science and Engineering, Massachusetts Institute of Technology, 77 Massachusetts Avenue, Cambridge, MA 02139, United States; email: coritz@mit.eduChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; silicon, 7440-21-3; thiol derivative, 13940-21-1; Biocompatible Materials; Durapatite, 1306-06-5; Silicon, 7440-21-3References: Carlisle, E.M., Silicon: A possible factor in bone calcification (1970) Science, 167, pp. 279-280;Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Gibson, I.R., Best, S.M., Bonfield, W., Effect of silicon substitution on the sintering and microstructure of hydroxyapatite (2002) J Am Ceram Soc, 85, pp. 2771-2777; Legeros, R.Z., LeGeros, J.P., Dense hydroxyapatite (1993) An Introduction to Bioceramics, pp. 139-180. , Hench LL, Wilson J, editors. Singapore: World Scientific; Van Raemdonck, W., Ducheyne, P., De Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Biomaterials, pp. 143-166. , Ducheyne P, Hastings G, editors. Boca Raton, FL: CRC Press; Botelho, C.M., Lopes, M.A., Gibson, I.R., Best, S.M., Santos, J.D., Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy (2002) J Mater Sci: Mater Med, 13, pp. 1123-1127; Gibson, I.R., Huang, J., Best, S.M., Bonfield, W., Enhanced in vitro cell activity and surface apatite layer formation on novel silicon-substituted hydroxyapatites (1999) Proceedings of the International Symposium on Ceramics in Medicine, Bioceramics 12, pp. 191-194. , Ohgushi H, Hastings GW, Yoshikawa T, editors. River Edge, NJ: World Scientific Publishing; Balas, F., Perez-Pariente, J., Vallet-Regi, M., In vitro bioactivity of silicon-substituted hydroxyapatites (2003) J Biomed Mater Res A, 66, pp. 364-375; Botelho, C.M., Brooks, R.A., Best, S.M., Lopes, M.A., Santos, J.D., Rushton, N., Bonfield, W., Biological and physical-chemical characterization of phase pure HA and Si-substituted hydroxyapatite by different microscopy techniques (2004) Proceedings of the International Symposium on Ceramics in Medicine, Bioceramics 16, pp. 845-848. , Barbosa MA, Monteiro FJ, Correia R, Leon B, editors. Uetikon-Zuerich, Switzerland: Trans Tech; Patel, N., Best, S.M., Bonfield, W., Gibson, I.R., Hing, K.A., Damien, E., Revel, P.A., A comparative study on the in vivo behavior of hydroxyapatite and silicon substituted hydroxyapatite granules (2002) J Mater Sci: Mater Med, 13, pp. 1199-1206; Porter, A.E., Patel, N., Skepper, J.N., Best, S.M., Bonfield, W., Effect of sintered silicate-substituted hydroxyapatite on remodeling process at the bone-implant interface (2004) Biomaterials, 25, pp. 3303-3314; Vandiver, J., Dean, D., Patel, N., Bonfield, W., Ortiz, C., Nanoscale variation in surface charge of synthetic hydroxyapatite detected by chemically and spatially specific high resolution force spectroscopy (2005) Biomaterials, 26, pp. 271-283; Ducheyne, P., Qiu, Q., Bioactive ceramics: The effect of surface reactivity on bone formation and bone cell function (1999) Biomaterials, 20, pp. 2287-2303; Dubok, V.A., Bioceramics - Yesterday, today, tomorrow (2000) Powder Metall Met Ceram, 39, pp. 381-394; Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, V.C.A., The ultrastructure of the bone-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J Biomed Mater Res, 27, pp. 999-1006; Kokubo, T., Kushitani, H., Sakka, S., Kitsugi, T., Yamamuro, T., Solutions able to reproduce in vivo surface-structure changes in bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 721-734; Himeno, T., Kim, H.-M., Kaneko, H., Kawashita, M., Kokubo, T., Nakamura, T., Surface structural changes of sintered hydroxyapatite in terms of surface charge (2003) Proceedings of the International Symposium on Ceramics in Medicine, Bioceramics 15, pp. 457-460. , Besim Ben-Nissan DS, William Walsh, editors. Uetikon-Zuerich, Switzerland: Trans Tech; Sato, K., Kumagai, Y., Tanaka, J., Apatite formation on organic monolayers in simulated body environment (2000) J Biomed Mater Res, 50, pp. 16-20; Tanahashi, M., Matsuda, T., Surface functional group dependence on apatite formation on self-assembled monolayers in a simulated body fluid (1997) J Biomed Mater Res, 34, pp. 305-315; Yamashita, K., Oikawa, N., Umegaki, T., Acceleration and deceleration of bone-like crystal growth on ceramic hydroxyapatite by electric poling (1996) Chem Mater, 8, pp. 2697-2700; Hwang, K.S., Song, J.E., Jo, J.W., Yang, H.S., Park, Y.J., Ong, J.L., Rants, H.R., Effect of poling conditions on growth of calcium phosphate crystal in ferroelectric BaTiO 3 ceramics (2002) J Mater Sci: Mater Med, 13, pp. 133-138; Ohgaki, M., Kizuki, T., Katsura, M., Yamashita, K., Manipulation of selective cell adhesion and growth by surface charges of electrically polarized hydroxyapatite (2001) J Biomed Mater Res, 57, pp. 366-373; Kobayashi, T., Nakamura, S., Yamashita, K., Enhanced osteobonding by negative surface charges of electrically polarized hydroxyapatite (2001) J Biomed Mater Res, 57, pp. 477-484; Parsegian, V.A., Gingell, D., On the electrostatic interaction across a salt solution between two bodies bearing unequal charges (1972) Biophys J, 12, pp. 1192-1204; Butt, H.J., Measuring electrostatic, van der Waals, and hydration forces in electrolyte-solutions with an atomic force microscope (1991) Biophys J, 60, pp. 1438-1444; Brown, P.W., Martin, R.I., An analysis of hydroxyapatite surface layer formation (1999) J Phys Chem B, 103, pp. 1671-1675; Noy, A., Vezenov, D.V., Lieber, C.M., Chemical force microscopy (1997) Annu Rev Mater Sci, 27, pp. 381-421; Israelachvili, J., (1991) Intermolecular and Surface Forces, , Amsterdam: Academic Press; Verwey, E.J.W., Overbeek, J.T.G., Nes, K.V., (1948) Theory of the Stability of Lyophobic Colloids, , New York: Elsevier; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812; Seog, J., Dean, D., Plass, A.H.K., Wong-Palms, S., Grodzinsky, A.J., Ortiz, C., Direct measurement of glycosaminoglycan intermolecular interactions via high-resolution force spectroscopy (2002) Macromolecules, 35, pp. 5601-5615; Ashby, P.D., Chen, L., Lieber, C.M., Probing intermolecular forces and potentials with magnetic feedback chemical force microscopy (2000) J Am Chem Soc, 122, pp. 9467-9472; Ederth, T., Computation of Lifshitz-van de Waals forces between alkylthiol monolayers on gold films (2001) Langmuir, 17, pp. 3329-3340; Forsythe, G.E., Wasow, W.R., (1960) Finite Difference Methods for Partial Differential Equations, , New York: Wiley; (1997) Principles of Colloid and Surface Chemistry, 3rd Ed., , Hiemenz P, Rajagopalan R, editors. New York: Marcel Dekker; Eichert, D., Combes, C., Drouet, C., Rey, C., Formation and evolution of hydrated surface layers of apatites (2005) Proceedings of the International Symposium on Ceramics in Medicine, Bioceramics 17, pp. 3-6. , Li P, Zhang K, Colwell C, editors. Uetikon-Zuerich, Switzerland: Trans Tech; Rixman, M., Dean, D., Macias, C., Ortiz, C., Nanoscale intermolecular interactions between human serum albumin and alkanethiol self-assembled monolayers (2003) Langmuir, 19, pp. 6202-6218; Ackler, H.D., French, R.H., Chiang, Y., Comparisons of Hamaker constants for ceramic systems with intervening vacuum or water: From force laws and physical properties (1996) J Colloid Interface Sci, 179, pp. 460-469; Kane, V., Mulvaney, P., Double-layer interactions between self-assembled monolayers of ω-mercaptoundecanoic acid on gold surfaces (1998) Langmuir, 14, pp. 3302-3311; Atkins, P., (1997) The Elements of Physical Chemistry, , New York: Freeman; Zhu, P.X., Masuda, Y., Koumoto, K., Site-selective adhesion of hydroxyapatite microparticles on charged surfaces in a super-saturated solution (2001) J Colloid Interface Sci, 243, pp. 31-36; James, M., Hunter, R.J., O'Brien, R.W., Effect of particle size distribution and aggregation on electroacoustic measurements of ξ potential (1992) Langmuir, 8, pp. 420-423; Toikka, G., Hayes, R.A., Ralston, J., Surface forces between spherical ZnS particles in aqueous electrolyte (1996) Langmuir, 12, pp. 3783-3788; Pedersen, H.G., Bergstrom, L., Forces measured between zirconia surfaces in poly(acrylic acid) solutions (1999) J Am Ceram Soc, 82, pp. 1137-1145; Cohen, M., Joester, D., Geiger, B., Addadi, L., Spatial and temporal sequence of events in cell adhesion: From molecular recognition to focal adhesion assembly (2004) Chem Bio Chem, 5, pp. 1393-1399; Smith, I.O., Baumann, M.J., McCabe, L.R., Electrostatic interactions as a predictor for osteoblast attachment to biomaterials (2004) J Biomed Mater Res A, 70, pp. 436-441; (1979) Plasma Proteins, , Blombaek B, Hanson L, editors. New York: Wiley; Porter, A.E., Hobbs, L.W., Rosen, V.B., Spector, M., The ultrastructure of the plasma-sprayed hydroxyapatite-bone interface predisposing to bone bonding (2002) Biomaterials, 23, pp. 725-733; Porter, A.E., Patel, N., Skepper, J.N., Best, S.M., Bonfield, W., Comparison of in vivo dissolution processes in hydroxyapatite and silicon-substituted hydroxyapatite bioceramics (2003) Biomaterials, 24, pp. 4609-4620
Keywords: Adhesives; article; Atomic force microscopy; Biocompatible Materials; biomaterial; Biomaterials; Bone; cell adhesion; chemical binding; chemical interaction; derjaguin landau verwey overbeek approximation; Durapatite; electrochemical analysis; Electrostatic; Electrostatics; high resolution force spectroscopy; hydroxyapatite; materials testing; mathematical analysis; Microscopy, Electron, Scanning; Monolayers; Nanomechanics; Nanostructures; Particle Size; Poisson distribution; Polycrystalline materials; Silicon; Silicon-substituted hydroxyapatite; Spectrophotometry; Spectroscopy; Spectroscopy, Fourier Transform Infrared; Stress, Mechanical; Surface charge; surface property; thiol derivative; Van der Waals; Van der Waals forces

Structural analysis of dextran-based hydrogels obtained chemoenzymatically - Ferreira, L.; Figueirecio, M.M.; Gil, M.H.; Ramos, M.A. (Journal of Biomedical Materials Research - Part B Applied BiomaterialsJ. Biomed. Mater. Res. Part B Appl. Biomater., 2006)
This work reports the results of structural analysis in novel dextran-acrylate (dexT70-VA) hydrogels generated chemoenzymatically. Porous structure as well as hydrogel surface and interior morphologies were evaluated by mercury intrusion porosimetry (MIP), nitrogen adsorption (NA), and scanning electron microscopy (SEM) analyses, as a function of the degree of substitution (DS), and initial water content used in the preparation of the hydrogel. MIP analysis showed that the overall networks were clearly macroporous with pore sizes ranging from 0.065 to 10 μm. As expected, the average pore size decreased as DS increased and as initial water content decreased. Moreover, the porosity values ranged from 75 up 90%, which shows that these hydrogels present an interconnected pore structure. Nitrogen adsorption analyses showed that the specific surface area of dexT70-VA hydrogels increased either by increasing the DS or by decreasing the initial water content of the hydrogel. SEM results revealed that the surface of hydrogels with lower DS presented either a porous structure or a polymeric "skin" covering the pores, whereas hydrogels with higher DS were totally porous. Furthermore, the interior morphology varied according to the DS and the initial water content of the hydrogels. Finally, the average pore size was also determined from the swelling of hydrogel using a theoretical model developed by FIory-Rehner. The comparison of the SEM and MIP results with the ones obtained by the equilibrium swelling theory of Flory-Rehner shows that this approach highly underestimates the average pore size. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JBMRGdoi: 10.1002/jbm.b.30394PubMed ID: 16211568Language of Original Document: EnglishCorrespondence Address: Ferreira, L.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: lino@mit.eduChemicals/CAS: acrylic acid, 10344-93-1, 79-10-7; dextran, 87915-38-6, 9014-78-2; nitrogen, 7727-37-9; Biocompatible Materials; Dextrans, 9004-54-0; Hydrogels; Nitrogen, 7727-37-9; Water, 7732-18-5References: Peppas, N.A., Bures, P., Leobandung, W., Ichikawa, H., Hydrogels in pharmaceutical formulations (2000) Eur J Pharm Biopharm, 50, pp. 27-46;Park, K., Park, H., Biocompatibility issues of implantable drug delivery systems (1996) Pharm Res, 13, pp. 1770-1776; Lee, K.Y., Mooney, D.J., Hydrogels for tissue engineering (2001) Chem Rev, 101, pp. 1869-1879; Nguyen, K.T., West, J.L., Photopolymerizable hydrogels for tissue engineering applications (2002) Biomaterials, 23, pp. 4307-4314; Meyvis, T., De Smedt, S., Stubbe, B., Hennink, W., Demeester, J., On the release of proteins degrading dextran methacrylate hydrogels and the correlation with the rheologic properties of the hydrogels (2001) Pharm Res, 18, pp. 1593-1599; Dziubla, T.D., Torjman, M.C., Joseph, J.I., Murphy-Tatum, M., Lowman, A.M., Evaluation of porous networks of poly(2-hydroxyethyl methacrylate) as interfacial drug delivery devices (2001) Biomaterials, 22, pp. 2893-2899; Jen, A.C., Wake, M.C., Mikos, A.G., Review: Hydrogels for cell immobilization (1996) Biotechnol Bioeng, 50, pp. 357-364; Silver, F.H., Wound dressings and skin replacement (1994) Biomaterials, Medical Devices and Tissue Engineering, pp. 47-91. , Silver FH, editor. London: Chapman & Hall; Iza, M., Woerly, S., Danumah, C., Kaliaguine, S., Bousmina, M., Determination of pore size distribution for mesoporous materials and polymeric gels by means of DSC measurements: Thermoporometry (2000) Polymer, 41, pp. 5885-5893; Everett, D.H., IUPAC manual of symbols and terminology for physicochemical quantities and units (1972) Pure Appl Chem, 31, pp. 579-638; Behravesh, E., Jo, S., Zygourakis, K., Mikos, A.G., Synthesis of in situ cross-linkable macroporous biodegradable poly(propylene fumarate-co-ethylene glycol) hydrogels (2002) Biomacromolecules, 3, pp. 374-381; Kim, S.-H., Chu, C.-C., Pore structure analysis of swollen dextranmethacrylate hydrogels by SEM and mercury intrusion porosimetry (2000) J Biomed Mater Res: Appl Biomater, 53, pp. 258-266; Kang, H.-W., Tabata, Y., Ikada, Y., Fabrication of porous gelatin scaffolds for tissue engineering (1999) Biomaterials, 20, pp. 1339-1344; Woerly, S., Marchand, R., Lavallée, C., Interactions of copolymeric poly(glyceryl methacrylate)-collagen hydrogels with neural tissue: Effects of structure and polar groups (1991) Biomaterials, 12, pp. 197-203; Woerly, S., Pinet, E., De Robertis, L., Bousmina, M., Laroche, G., Roitback, T., Vargová, L., Syková, E., Heterogeneous PHPMA hydrogel for tissue repair and axonal regeneration in the injured spinal cord (1998) Polymers for Tissue Engineering, pp. 343-373. , Schoichet MS, Hubbell JA, editors. Utrecht: VSP; Ferreira, L., Gil, M.H., Dordick, J.S., Enzymatic synthesis of dextran-containing hydrogels (2002) Biomaterials, 23, pp. 3957-3967; Flory, P.J., Rehner, R., Statistical mechanics of cross-linked polymer networks. II. Swelling (1943) J Chem Phys, 11, pp. 521-526; Peppas, N.A., Moynihan, H.J., Lucht, L.M., The structure of highly crosslinked poly(2-hydroxyethylmethacrylate) hydrogels (1985) J Biomed Mater Res, 19, pp. 397-411; Canal, T., Peppas, N.A., Correlation between mesh size and equilibrium degree of swelling of polymeric networks (1989) J Biomed Mater Res, 23, pp. 1183-1193; Hennink, W.E., Talsma, H., Borchert, J.C.H., De Smedt, S.C., Demmester, J., Controlled release of proteins from dextran hydrogels (1996) J Control Release, 39, pp. 47-55; Stringer, J.L., Peppas, N.A., Diffusion of small molecular weight drugs in radiation-crosslinked poly(ethylene oxide) hydrogels (1996) J Control Release, 42, pp. 195-202; Washburn, E.W., Note on a method of determining the distribution of pore sizes in a porous material (1921) Proc Natl Acad Sci USA, 7, pp. 115-116; Brunauer, S., Emmett, P.H., Teller, E., Adsorption of gases in multimolecular layers (1938) J Am Chem Soc, 60, pp. 309-319; Barrett, E.P., Joyner, L.G., Hallendo, P.B., The determination of pore volume and area distributions in porous substances-I. Computations from nitrogen isotherms (1951) J Am Chem Soc, 73, pp. 373-380; Meyvis, T.K.L., De Smedt, S.C., Demeester, J., Hennink, W.E., Rheological monitoring of long-term degrading polymer hydrogels (1999) J Rheol, 43, pp. 933-950; Ferreira, L., Rafael, A., Lamghari, M., Barbosa, M.A., Gil, M.H., Cabrita, A.M.S., Dordick, J.S., Biocompatibility of chemoenzymatically derived dextran-acrylate hydrogels (2004) J Biomed Mater Res, 68, pp. 584-596; Gregg, S.J., Sing, K.S.W., (1991) Adsorption, Surface Area and Porosimetry. 2nd Ed., , London: Academic Press Inc; Van Brackel, J., Modry, S., Svatá, M., Mercury porosimetry: State of the art (1981) Powder Technol, 29, pp. 1-12; Moscou, L., Lub, S., Practical use of mercury porosimetry in the study of porous solids (1981) Powder Technol, 29, pp. 45-52; Chirila, T.V., Constable, I.J., Crawford, G.J., Vijayasekaran, S., Thompson, D.E., Chen, Y.-C., Fletcher, W.A., Griffin, B.J., Poly(2-hydroxyethyl methacrylate) sponges as implant materials: In vivo and in vitro evaluation of cellular invasion (1993) Biomaterials, 14, pp. 26-38; Lustig, S.R., Peppas, N.A., Solute diffusion in swollen membranes. IX. Scaling laws for solute diffusion in gels (1988) J Appl Polym Sci, 36, pp. 735-747; Reinhart, C.T., Peppas, N.A., Solute diffusion in swollen membranes. Part II. Influence of crosslinking on diffusive properties (1984) J Membr Sci, 18, pp. 227-239; Bell, C.L., Peppas, N.A., Biomedical membranes from hydrogels and interpolymer complexes (1995) Adv Polym Sci, 122, pp. 125-175
Keywords: acrylic acid; article; Biocompatible Materials; Chemical structure; Degree of substitution (DS); dextran; dextran acrylate; Dextrans; enzyme activity; Enzymes; equilibrium swelling theory; Gas adsorption; hydrogel; Hydrogels; materials testing; Mathematical models; Mercury intrusion porosimetry; Microscopy, Electron, Scanning; Molecular Structure; morphology; nitrogen; polymer; porosity; Scanning electron microscopy; Structural characterization; structure analysis; Surface Properties; theoretical model; unclassified drug; Water; water content

Three-dimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation - Amaral, I.F.; Sampaio, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
In this investigation, the effect of the degree of acetylation (DA) of chitosan on the behavior of human osteoblastic MG-63 cells cultured in three-dimensional chitosan matrices was assessed. Chitosan sponges with DAs in the range of 4 to 49% were prepared and characterized in terms of microstructure, porosity, and pore size. Collagen sponges were used as 3D control. Cell proliferation was determined using the MTT assay while the retention of the osteoblastic phenotype was monitored by assaying alkaline phosphatase activity. Cell morphology, cytoskeletal organization, and viability were assessed using different microscopy techniques. Chitosan sponges showed a similar microstructure regardless the DA, except for the highest DA used, where a more heterogeneous pore distribution was observed. In terms of cell proliferation, alkaline phosphatase activity and cell viability, cells cultured in chitosan scaffolds performed as well as in the 3D control regardless the DA, except for the highest DA used, where an inhibitory effect on cell proliferation was found. However, while in sponges with DAs ≤ 13% cells attached and spread displaying long cell filopodia and numerous cell-to-cell contacts, in sponges with higher DAs cells tended to remain spherical and grow into spheroid-like cellular aggregates. In the present study, the DA played a key role in determining the affinity of osteoblastic cells towards the substrates, possibly by influencing the nature of the initial adsorbed protein layer. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30522PubMed ID: 16270345Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; chitosan, 9012-76-4; collagen, 9007-34-5; Alkaline Phosphatase, EC 3.1.3.1; Chitosan, 9012-76-4; Collagen, 9007-34-5References: Bruder, S.P., Caplan, A.I., Bone regeneration through cellular engineering (2000) Principles of Tissue Engineering, pp. 683-696. , Lanza RP, Langer R, Vacanti J, editors. San Diego: Academic Press;Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; Khor, E., (2001) Chitin: Fulfilling a Biomaterials Promise, , Oxford, UK: Elsevier Science Ltd; Vandevord, P.J., Hwt, M., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59, pp. 585-590; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18, pp. 567-575; Rao, S.B., Sharma, C.P., Sterilization of chitosan: Implications (1995) J Biomater Appl, 10, pp. 136-143; Muzzarelli, R.A.A., Zucchini, C., Ilari, P., Pugnaloni, A., Belmonte, M.M., Biagini, G., Castaldini, C., Osteoconductive properties of methylpyrrolidinone chitosan in an animal-model (1993) Biomaterials, 14, pp. 925-929; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Control Release, 78, pp. 187-197; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., Preparation and histological evaluation of biomimetic three-dimensional hydroxyapatite/chitosan-gelatin network composite scaffolds (2002) Biomaterials, 23, pp. 3227-3234; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Eng, 8, pp. 1009-1016; Zhang, Y., Zhang, M.Q., Calcium phosphate/chitosan composite scaffolds for controlled in vitro antibiotic drug release (2002) J Biomed Mater Res, 62, pp. 378-386; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., Cellular responses to chitosan in vitro: The importance of deacetylation (2000) J Mater Sci Mater Med, 11, pp. 773-778; Chatelet, C., Damour, O., Domard, A., Influence of the degree of acetylation on some biological properties of chitosan films (2001) Biomaterials, 22, pp. 261-268; Dhiman, H.K., Ray, A.R., Panda, A.K., Characterization and evaluation of chitosan matrix for in vitro growth of MCF-7 breast cancer cell lines (2004) Biomaterials, 25, pp. 5147-5154; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cells osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation (2005) J Biomed Mater Res Part A, 75 A, pp. 387-397; Cukierman, E., Pankov, R., Stevens, D.R., Yamada, K.M., Taking cell-matrix adhesions to the third dimension (2001) Science, 294, pp. 1708-1712; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., Highly deacetylated chitosan and its properties (1983) J Appl Polym Sci, 28, pp. 1909-1917; Aiba, S., Studies on Chitosan: 1. Determination of the degree of N-acetylation of chitosan by ultraviolet spectrophotometry and gel-permeation chromatography (1986) Int J Biol Macromol, 8, pp. 173-176; Hirano, S., Ohe, Y., Ono, H., Selective N-acylation of chitosan (1976) Carbohydr Res, 47, pp. 315-320; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., Improved method for Ir determination of the degree of N-acetylation of chitosan (1992) Int J Biol Macromol, 14, pp. 166-169; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29, pp. 63-68; Zhang, R.Y., Ma, P.X., Poly(alpha-hydroxyl acids) hydroxyapatite porous composites for bone-tissue engineering. I. Preparation and morphology (1999) J Biomed Mater Res, 44, pp. 446-455; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Ashton, B.A., Abdullah, F., Cave, J., Williamson, M., Sykes, B.C., Couch, M., Poser, J.W., Characterization of cells with high alkaline-phosphatase activity derived from human-bone and marrow - Preliminary assessment of their osteogenicity (1985) Bone, 6, pp. 313-319; Kurita, K., Controlled functionalization of the polysaccharide chitin (2001) Prog Polym Sci, 26, pp. 1921-1971; Wang, W., Bo, S.Q., Li, S.Q., Qin, W., Determination of the Mark-Houwink equation for chitosans with different degrees of deacetylation (1991) Int J Biol Macromol, 13, pp. 281-285; Roberts, G.A.F., (1992) Chitin Chemistry, , Houndmills: The Macmillan Press Ltd; Ueda, H., Hong, L., Yamamoto, M., Shigeno, K., Inoue, M., Toba, T., Yoshitani, M., Shimizu, Y., Use of collagen sponge incorporating transforming growth factor-beta 1 to promote bone repair in skull defects in rabbits (2002) Biomaterials, 23, pp. 1003-1010; Hanthamrongwit, M., Grant, M.H., Wilkinson, R., Confocal laser-scanning microscopy (Clsm) for the study of collagen sponge microstructure (1994) J Biomed Mater Res, 28, pp. 213-216; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., Time-dependent morphology and adhesion of osteoblastic cells on titanium model surfaces featuring scale-resolved topography (2004) Biomaterials, 25, pp. 2695-2711; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with 2 different pore-size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic-study of bony ingrowth and implant substitution (1988) Clin Orthop, 232, pp. 127-138; Madihally, S.V., Matthew, H.W.T., Porous chitosan scaffolds for tissue engineering (1999) Biomaterials, 20, pp. 1133-1142; Madihally, S.V., Frattaroli, T.L., Matthew, H.W.T., (1999) In Vivo Colonization of Chitosan Based Porous Scaffolds, p. 172. , Providence, RI: Transactions from the 25th Annual Meeting of the Society for Biomaterials, Providence, RI; Zhang, Y., Zhang, M.Q., Synthesis and characterization of macroporous chitosan/calcium phosphate composite scaffolds for tissue engineering (2001) J Biomed Mater Res, 55, pp. 304-312; Chung, T.W., Yang, J., Akaike, T., Cho, K.Y., Nah, J.W., Kim, S.I., Cho, C.S., Preparation of alginate/galactosylated chitosan scaffold for hepatocyte attachment (2002) Biomaterials, 23, pp. 2827-2834; Masi, L., Franchi, A., Santucci, M., Danielli, D., Arganini, L., Giannone, V., Formigli, L., Beghe, F., Adhesion, growth, and matrix production by osteoblasts on collagen substrata (1992) Calcif Tissue Int, 51, pp. 202-212; Wiesmann, H.P., Nazer, N., Klatt, C., Szuwart, T., Meyer, U., Bone tissue engineering by primary osteoblast-like cells in a monolayer system and 3-dimensional collagen gel (2003) J Oral Maxillofac Surg, 61, pp. 1455-1462; Henriksen, I., Green, K.L., Smart, J.D., Smistad, G., Karlsen, J., Bioadhesion of hydrated chitosans: An in vitro and in vivo study (1996) Int J Pharmaceut, 145, pp. 231-240; Lebaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: Functional applications in orthopedic materials (2000) Tissue Eng, 6, pp. 85-103; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: Consequences for valve endothelial cell growth on tissue-engineering materials (2003) J Biomed Mater Res Part A, 67 A, pp. 538-547; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res Part A, 66 A, pp. 247-259; Webb, K., Hlady, V., Tresco, P.A., Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces (2000) J Biomed Mater Res, 49, pp. 362-368; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Lost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Domard, A., Chitosan interactions (1997) Advances in Chitin Science, pp. 410-420. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher;
Keywords: Acetylation; Aggregates; alkaline phosphatase; article; Bone Regeneration; bone tissue; Bone tissue engineering; Cell culture; Cell Culture Techniques; Cell filopodia; cell growth; cell proliferation; Cell Shape; cell structure; cell survival; cell viability; chitosan; Collagen; confocal microscopy; controlled study; Cytoskeletal organization; cytoskeleton; Degree of acetylation (DA); enzyme activity; gel permeation chromatography; human; human cell; Humans; infrared spectroscopy; Microstructure; morphology; osteoblast; Osteoblastic cells; Osteoblasts; Phosphatase activity; porosity; Proteins; Scaffold; Scaffolds; Scanning electron microscopy; Substrates; Tissue engineering

Time-lapse analysis of stem-cell divisions in the Arabidopsis thaliana root meristem - Campilho, A.; Garcia, B.; Toorn, H.V.D.; Wijk, H.V.; Campilho, A.; Scheres, B. (Plant JournalPlant J., 2006)
In the Arabidopsis root, asymmetric stem-cell divisions produce daughters that form the different root cell types. Here we report the establishment of a confocal tracking system that allows the analysis of numbers and orientations of cell divisions in root stem cells. The system provides direct evidence that stem cells have lower division rates than cells in the proximal meristem. It also allows tracking of cell division timing, which we have used to analyse the synchronization of root cap divisions. Finally, it gives new insights into lateral root cap formation: epidermal stem-cell daughters can rotate the orientation of the division plane like the stem cell. © 2006 The Authors.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: PLJUEdoi: 10.1111/j.1365-313X.2006.02892.xPubMed ID: 17087761Language of Original Document: EnglishCorrespondence Address: Scheres, B.; Department of Molecular Genetics, University of Utrecht, Utrecht, Netherlands; email: b.scheres@bio.uu.nlReferences: Aida, M., Beis, D., Heidstra, R., Willemsen, V., Blilou, I., Galinha, C., Nussaume, L., Scheres, B., The PLETHORA genes mediate patterning of the Arabidopsis root stem cell niche (2004) Cell, 119, pp. 109-120;Baskin, T.I., On the constancy of cell-division rate in the root meristem (2000) Plant Mol. Biol., 43, pp. 545-554; Van Den Berg, C., Willemsen, V., Hendriks, G., Weisbeek, P., Scheres, B., Short-range control of cell differentiation in the Arabidopsis root meristem (1997) Nature, 390, pp. 287-289; Van Den Berg, C., Hage, W., Weisbeek, P., Scheres, B., Laser ablation in Arabidopsis roots: A tool to study cell-to-cell communication (1998) NATO ASI Ser., H104, pp. 237-250; Boisnard-Lorig, C., Colon-Carmona, A., Bauch, M., Hodge, S., Doerner, P., Bancharel, E., Dumas, C., Berger, F., Dynamic analyses of the expression of the HISTONE::YFP fusion protein in Arabidopsis show that syncytial endosperm is divided in mitotic domains (2001) Plant Cell, 13, pp. 495-509; Buvat, R., Structure, evolution et functionnement du méristèm apical de quelques dicotylédones (1952) Ann. Sci. Nat. Bot. Ser., 13, pp. 199-300; Clough, S.J., Bent, A.F., Floral dip: A simplified method for Agrobacterium-mediated transformation of Arabidopsis thaliana (1998) Plant J., 16, pp. 735-743; Clowes, F.A.L., Nucleic acids in root apical meristems of Zea (1956) New Phytol., 55, pp. 29-34; Cutler, S.R., Ehrhardt, D.W., Griffitts, J.S., Somerville, C.R., Random GFP::cDNA fusions enable visualization of subcellular structures in cells of Arabidopsis at a high frequency (2000) Proc. Natl Acad. Sci. USA, 97, pp. 3718-3723; Dolan, L., Janmaat, K., Willemsen, V., Linstead, P., Poethig, S., Roberts, K., Scheres, B., Cellular organization of the Arabidopsis thaliana root (1993) Development, 119, pp. 71-84; Dolan, L., Duckett, C.M., Grierson, C., Linstead, P., Schneider, K., Lawson, E., Dean, C., Roberts, K., Clonal relationships and cell patterning in the root epidermis of Arabidopsis (1994) Development, 120, pp. 2465-2474; Dolznig, H., Grebien, F., Sauer, T., Beug, H., Mullner, E.W., Evidence for a size-sensing mechanism in animal cells (2004) Nat. Cell Biol., 6, pp. 899-905; Furner, I.J., Pumfrey, J.E., Cell fate in the shoot apical meristem of Arabidopsis thaliana (1992) Development, 115, pp. 755-764; Garcia, B., Campilho, A., Scheres, B., Campilho, A., Automatic tracking of Arabidopsis thaliana root meristem in confocal microscopy (2004) ICIAR 2004 LNCS 3212, pp. 166-174. , (Campilho, A. and Kamel, M., eds). New York, Springer Verlag; Irish, V.F., Sussex, I.M., A fate map of the Arabidopsis embryonic shoot apical meristem (1992) Development, 115, pp. 745-753; Jorgensen, P., Nishikawa, J., Breitkreutz, B.J., Tyers, M., Systematic identification of pathways that couple cell growth and division in yeast (2002) Science, 297, pp. 395-400; Nance, J., Priess, J.R., Cell polarity and gastrulation in C. elegans (2002) Development, 129, pp. 387-397; O'Connell, K.F., Leys, C.M., White, J.G., A genetic screen for temperature-sensitive cell-division mutants of Caenorhabditis elegans (1998) Genetics, 149, pp. 1303-1321; Otsu, N., A threshold selection method from gray level histograms (1979) IEEE Trans. Syst. Man. Cybernet., 9, pp. 62-66; Perona, P., Malik, J., Scale space and edge detection using anisotropic diffusion (1990) IEEE Trans. Pattern Anal. Mach. Intel., 12, pp. 629-639; Reddy, G.V., Heisler, M.G., Ehrhardt, D.W., Meyerowitz, E.M., Real-time lineage analysis reveals oriented cell divisions associated with morphogenesis at the shoot apex of Arabidopsis thaliana (2004) Development, 131, pp. 4225-4237; Sabatini, S., Heidstra, R., Wildwater, M., Scheres, B., SCARECROW is involved in positioning the stem cell niche in the Arabidopsis root meristem (2003) Genes Dev., 17, pp. 354-358; Scheres, B., Wolkenfelt, H., Willemsen, V., Terlouw, M., Lawson, E., Dean, C., Weisbeek, P., Embryonic origin of the Arabidopsis primary root and root meristem initials (1994) Development, 120, pp. 2475-2487; Sulston, J.E., Schierenberg, E., White, J.G., Thomson, J.N., The embryonic cell lineage of the nematode Caenorhabditis elegans (1983) Dev. Biol., 100, pp. 64-119; Thomas, C., Devries, P., Hardin, J., White, J., Four-dimensional imaging: Computer visualization of 3D movements in living specimens (1996) Science, 273, pp. 603-607; Watt, F., Hogan, B., Out of Eden: Stem cells and their niches (2000) Science, 287, pp. 1427-1430; Wildwater, M., Campilho, A., Perez-Perez, J.M., Heidstra, R., Blilou, I., Korthout, H., Chatterjee, J., Scheres, B., The RETINOBLASTOMA-RELATED gene regulates stem cell maintenance in Arabidopsis (2005) Cell, 123, pp. 1337-1349
Keywords: Arabidopsis; Arabidopsis thaliana; article; cell cycle; Cell Division; Cells; cytology; Development; Growth; Growth kinetics; Image analysis; meristem; Photoperiod; photoperiodicity; Plant; plant root; Plant roots; Plants; Plants (botany); Real-time; stem cell; Stem cells; Stem-cell daughters; time; Time Factors

Titanium dental implants coated with Bonelike®: Clinical case report - Lobato, J.V.; Sooraj Hussain, N.; Botelho, C.M.; Maurício, A.C.; Lobato, J.M.; Lopes, M.A.; Afonso, A.; Ali, N.; Santos, J.D. (Thin Solid FilmsThin Solid Films, 2006)
The aim of the study was to evaluate the direct bone bonding and osteointegration of the commercial pure (cp Ti) implants coated with Bonelike® synthetic bone graft by plasma spraying. The Bonelike® coated implant was placed in the mandible of a 40-year-old patient and it was removed after a healing period of 3 months with a trephine of 6 mm diameter. The structure of the coating and new bone/implant interface of retrieved samples were evaluated using scanning electron microscopy (SEM) and histological analysis using light microscopy. In vivo microstructure observations of Bonelike® coated retrieved implants showed excellent bone remnants on its surface without any tissue and inflammatory signs observed. The reported Bonelike® coated (cp Ti) implants improved primary stability, which may increase the lifetime of the implant. Bonelike® coated dental implants proved to be highly bioactive with extensive new bone formation and strongly bonded to Bonelike® coating. © 2005 Elsevier B.V. All rights reserved.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2005.12.151Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Murugan, R., Ramakrishna, S., (2005) Compos. Sci. Technol., 65, p. 2385;Boyle, W.J., Simonet, W.S., Lacey, D.L., (2003) Nature, 423, p. 337; Karabuda, C., Ozdemir, O., Tosun, T., Anil, A., Olgac, V., (2001) J. Periodontol., 72, p. 1436; Placko, H.E., Mishra, S., Weimer, J.J., Lucas, L.C., (2000) Int. J. Oral Maxillofac. Implants, 15, p. 355; Jung, Y.C., Han, C.H., Lee, I.S., Kim, H.E., (2001) Int. J. Oral Maxillofac. Implants, 16, p. 809; Kong, Y.M., Kim, D.H., Kim, H.E., Heo, S.J., Koak, J.Y., (2002) J. Biomed. Mater. Res., Part B Appl. Biomater., 63, p. 714; Schutz, R.W., Thomas, D.E., (1987) Metals Handbook. ed. 9, 13, p. 669. , Davis J.R. (Ed), American Society for Metals, Cleveland, OH; Tsui, Y.C., Doyle, C., Clyne, T.W., (1998) Biomaterials, 19, p. 2015; Lavos-Valereto, I.C., Wolynec, S., Deboni, M.C.Z., Konig Jr., B., (2001) J. Biomed. Mater. Res., Part B Appl. Biomater., 58, p. 727; Lacefield, W.R., (1993) An Introduction to Bioceramics, , Hench L.L., and Wilsion J. (Eds), World Scientific, Singapore; Golec, T.S., Krauser, J.T., (1992) Dent. Clin. North Am., 36, p. 39; Block, M.S., Kkent, J.N., (1992) Dent. Clin. North Am., 36, p. 27; Yukna, R.A., (1992) Dent. Clin. North Am., 36, p. 97; Baltag, I., Watanabe, K., Kusakari, H., Taoyuki, N., Miyakawa, O., Kobayashi, M., Ito, N., (2000) J. Biomed. Mater. Res., Part B Appl. Biomater., 53, p. 76; Wheeler, S.L., (1996) Int. J. Oral Maxillofac. Implants, 11, p. 340; Tsui, Y.C., Doyle, C., Clyne, T.W., (1998) Biomaterials, 19, p. 2031; (1981) Science and Medical Applications of Hydroxyapatite, , Conish H., Aoki H., and Sawai K. (Eds), Takyama Press Systems Centre Co., Tokyo; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Lakhan, J.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 21, p. 749; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Oslen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci., Mater. Med., 12, p. 629; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, p. 3105; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) Surf. Coat. Technol., 102, p. 191; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (1999) J. Mater. Sci., Mater. Med., 10, p. 567; Lobato, J.V., Sooraj Hussain, N., Sousa, R.C., Maurício, A.C., Santos, J.D., (2005) Br. J. Oral Maxillofac. Surg., , (Communicated); Bränemark, P.I., Svensson, B., van Steenberghe, D., (1995) Clin. Oral Implants Res., 6 (4), p. 227; Strnad, Z., Strand, J., Povysil, C., Urban, K.K., (2000) Int. J. Oral Maxillofac. Implants, 15, p. 483; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology, a Text and Atlas. ed. 3, , Williams & Wilkins, New York
Keywords: Bone; Bone Regeneration; Bone/implant interface; Bonelike® coatings; Clinical applications; Dental Implants; Dental prostheses; Hip prostheses; Medical applications; Optical microscopy; Plasma spraying

The uptake of titanium ions by hydroxyapatite particles - Structural changes and possible mechanisms - Ribeiro, C.C.; Gibson, I.; Barbosa, M.A. (BiomaterialsBiomaterials, 2006)
In order to understand the effect of titanium ions on the molecular structure of hydroxyapatite (HAp), HAp powders were incubated in solutions with different titanium concentrations. After incubation, the powders obtained were analysed using different techniques, namely X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), differential thermal analysis (DTA), X-ray photoelectron spectroscopy (XPS), and energy dispersive spectroscopy (EDS). The results suggest that, depending on the concentration of titanium in solution, two different mechanisms of interaction with HAp occur. For concentrations equal to or smaller than 200 ppm, the titanium uptake by the solid seems to be primarily due to incorporation in the lattice. For higher concentrations, a dissolution-precipitation process seems to occur, leading to formation of a titanium phosphate compound. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 44Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2005.09.043PubMed ID: 16256192Language of Original Document: EnglishCorrespondence Address: Ribeiro, C.C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: cribeiro@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; titanium, 7440-32-6; Biocompatible Materials; Durapatite, 1306-06-5; Ions; Solutions; titanium phosphate, 17017-57-1; Titanium, 7440-32-6References: Fowler, B.O., Infrared studies of apatites. II Preparation of normal and isotopically substituted calcium, strontium, and barium hydroxyapatites and spectra-structure-composition correlations (1974) Inorg Chem, 13, pp. 207-214;Legeros, R.Z., Daculsi, G., Orly, I., Abergas, T., Torres, W., Solution mediated transformation of octacalcium phosphate (OCP) to apatite (1989) Scann Microsc, 3, pp. 129-138; Takahashi, H., Yashima, M., Kakihana, M., Yoshimura, M., Synthesis of stoichiometric hydroxyapatite by a "gel" route from the aqueous solution of citric and phosphonoacetic acids (1995) Eur J Solid State Inorg Chem, 32, pp. 829-835; Posner, A.S., Blumenthal, N., Betts, F., Chemistry and structure of precipitated hydroxyapatites (1984) Phosphate Minerals, pp. 330-347. , J.O. Nriagu P.B. Moore Springer New York; Yamashita, K., Kanazawa, T., Hydroxyapatite (1989) Inorganic Phosphate Materials, pp. 15-54. , T. Kanazawa Kodansha Tokyo; Legros, R., Balmain, N., Bonel, G., Age related changes in mineral of rat and bovine cortical bone (1987) Calcif Tissue Int, 41, pp. 137-144; Legeros, R.Z., Quirolgico, G., Legeros, J.P., Trace elements: Incorporation of monovalent cations, Na +, K +, Li + (1981) J Dent Res, 60, pp. 452-458; Christoffersen, J., Christoffersen, M.R., Kolthoff, N., Barenholdt, O., Effects of strontium ions on growth and dissolution of hydroxyapatite and on bone mineral detection (1997) Bone, 20, pp. 47-54; Suzuki, T., Hatsushika, T., Hayakawa, Y., Synthetic hydroxyapatites employed as inorganic cation-exchangers (1981) J Chem Soc Faraday Trans, 77, pp. 1059-1062; Miyake, M., Ishigaki, K., Suzuki, T., Structure refinements of Pb2+ ion exchanged apatites by X-ray powder pattern-fitting (1986) J Solid State Chem, 61, pp. 230-235; Ergun, C., Webster, T.J., Bizios, R., Doremus, R.H., Hydroxylapatite with substituted magnesium, zinc, cadmium, and yttrium I. Structure and microstructure (2002) J Biomed Mater Res, 59, pp. 305-311; Bonel, G., Montel, G., Sur une nouvelle apatite carbonatée synthétique (1964) Compt Rend, 258, pp. 923-926; Legeros, R.Z., Singer, L., Ophaug, R.H., Quirolgico, G., Thein, A., Legeros, J.P., The effect of fluoride on the stability of synthetic and biological (bone) mineral apatites (1982) Osteoporosis, pp. 327-341. , J. Menczel G.C. Robin M. Makin R. Steinbeg Wiley New York; Kreidler, E.R., Hummel, F.A., The crystal chemistry of apatite: Structure fields of fluor and chloroapatite (1970) Am Mineral, 55, pp. 171-184; LeGeros, R.Z., Trautz, O.R., LeGeros, J.P., Klein, E., Carbonate substitution in the apatite structure (1) (1968) Extrait du Bulletin de la Societé Chimique de France, (SPEC. NO.), pp. 1712-1718; Azimov, S.Y., Ismatov, A.A., Fedorov, N.F., Synthetic silicophosphates, silicovanadates, and silicoarsenates with the apatite structure (1981) Inorg Mater, 17, pp. 1384-1387; Termine, J.D., Lundy, D.R., Hydroxide and carbonate in rat bone mineral and its synthetic analogues (1973) Calcif Tissue Res, 13, pp. 73-78; Lacout, J.L., Nounah, A., Ferhat, M., Strontium-cadmium substitution in hydroxy-and fluor-apatites (1998) Ann Chim Sci Mater, 23, pp. 57-60; El Feki, H., Savariault, J.M., Ben Salah, A., Structure refinements by Rietveld method of partially substituted hydroxyapatite: Ca 9Na 0.5(PO 4) 4.5(CO 3) 1.5(OH) 2 (1999) J Alloys Compounds, 287, pp. 114-120; Legeros, R.Z., Apatites in biological systems (1981) Prog Cryst Growth Charact, 4, pp. 1-45; Rey, C., Calcium phosphates for medical applications (1998) Calcium Phosphates in Biological and Industrial Systems, pp. 217-251. , A. Zahid Kluwer Academic Publishers Boston; Watanabe, T., Makitsuru, K., Nakazawa, H., Hara, S., Suehiro, T., Yamamoto, A., Separation of double strand DNA fragments by high-performance liquid chromatography using a ceramic hydroxyapatite column (1999) Anal Chim Acta, 386, pp. 69-75; Bett, J.A.S., Christner, L.G., Hall, W.K., Studies of the hydrogen held by solids. XII (1967) J Am Chem Soc, 89, pp. 5535-5541; Takeuchi, Y., Arai, H., Removal of coexisting Pb 2+, Cu 2+ and Cd 2+ ions from water by addition of hydroxyapatite powder (1990) J Chem Eng Japan, 23, pp. 75-80; Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterisation of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Legeros, R.Z., Ultrastructural properties of human enamel apatite (1983) Handbook of Experimental Aspects of Oral Biochemistry, pp. 159-179. , E.P. Lazzari CRC Press FL; Young, R.A., Elliott, J.C., Atomic-scale bases for several properties of apatites (1966) Archs Oral Biol, 11, pp. 699-707; Elliott, J.C., The problems of the composition and structure of the mineral components of hard tissues (1973) Clin Orthoped, 93, pp. 313-317; Christofferson, M.R., Thyregod, H.C., Cristofferson, J., Effects of aluminum (III), chromium (III) and iron (III) on the rate of dissolution of calcium hydroxyapatite crystals in the absence and presence of chelating agent desferrioxamine (1987) Calcif Tissue Int, 41, pp. 27-30; Posner, A.S., Blumenthal, N.C., In vitro model of aluminum-induced osteomalacia: Inhibition of hydroxyapatite formation and growth (1984) Calcif Tissue Int, 36, pp. 439-441; Levin, S.M., Goldberg, M., Clinical evaluation and management of lead-exposed construction workers (2000) Am J Ind Med, 37, pp. 23-43; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, pp. 52-54. , H. Aoki Takayama Press System Center Tokyo; Kay, M.I., Young, R.A., Posner, A.S., Crystal structure of hydroxyapatite (1964) Nature, 204, pp. 1050-1052; Stavitzky, A., Golay, M.J.E., Smoothing and differentiation of data by simplified least squares procedures (1964) Anal Chem, 36, pp. 1627-1639; Elliot, J.C., (1994) Structure and Chemistry of the Apatites and Other Calcium Orthophosphates, , J.C. Elliot Elsevier Amsterdam; Morgan, H., Wilson, R.M., Elliot, J.C., Dowker, S.E.P., Anderson, P., Preparation and characterisation of monoclinic hydroxyapatite and its precipitated carbonate apatite intermediate (2000) Biomaterials, 21, pp. 617-627; Nakamoto, K., (1978) Infrared and Raman Spectra of Inorganic and Coordination Compounds, , K. Nakamoto Wiley New York; Legeros, R.Z., Bonel, G., Legros, R., Types of "h 2O" in human enamel and in precipitated apatites (1978) Calcif Tissue Res, 26, pp. 111-118; Joris, S.J., Amberg, C.H., The nature of deficiency in non-stoichiometric hydroxyapatites II. Spectroscopic studies of calcium and strontium hydroxyapatites (1971) J Phys Chem, 75, pp. 3172-3178; Leung, Y., Walters, M.A., Legeros, R.Z., Second derivative infrared spectra of hydroxyapatite (1990) Spectroc Acta, 46 (10), pp. 1453-1459; Miller, L.M., Vaiaravamurthy, V., Chance, M.R., Mendelshon, R., Paschalis, E.P., Betts, F., In situ analysis of mineral content and crystallinity in bone using infrared micro-spectroscopy of the ν 4 PO 4 3- vibration (2001) Biochim Biophys Acta, 1527, pp. 11-19; Fowler, B.O., Infrared studies of apatites I. Vibrational assignments for calcium, strontium and barium hydroxyapatites utilizing isotopic substitutions (1974) Inorg Chem, 13, pp. 194-207; Fowler, B.O., Moreno, E.C., Brown, W.E., Infra-red spectra of hydroxyapatite, octacalcium phosphate and pyrolised calcium phosphate (1966) Arch Oral Biol, 11, pp. 477-492; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 3 PO 4 3- domain (1991) Calcif Tissue Int, 49, pp. 383-388; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 4 PO 4 3- domain (1990) Calcif Tissue Int, 46, pp. 384-394; Gadaleta, S.J., Paschalis, E.P., Betts, F., Mendelsohn, R., Boskey, A.L., Fourier transform infrared spectroscopy of the solution-mediated conversion of amorphous calcium phosphate to hydroxyapatite: New correlations between X-ray diffraction and infrared data (1996) Calcif Tissue Int, 58, pp. 9-16; Bailey, R.T., Holt, C., Fourier transform infrared spectroscopy and characterisation of biological calcium phosphates (1989) Calcified Tissues, pp. 93-120. , D.W.L. Hukins Macmillan Press Basingstoke; Baddiel, C.B., Berry, E.E., Spectra structure correlations in hydroxy and fluorapatite (1966) Spectroc Acta, 22, pp. 1407-1416; Paschalis, E.P., Di Carlo, E., Betts, F., Sherman, P., Mendelsohn, R., Boskey, A.L., FTIR Microspectroscopic analysis of human osteonal bone (1996) Calcif Tissue Int, 59, pp. 480-487; Gibson, I.R., Rehman, I., Best, S.M., Bonfield, W., Characterization of the transformation from calcium-deficient apatite to β-tricalcium phosphate (2000) J Mater Sci: Mater Med, 12, pp. 799-804; Szirtes, L., Riess, L., Megyeri, J., Thermoanalytical investigation of layered titanium salts (2003) J Thermal Anal Calorim, 73, pp. 209-218; Schroeder, L.W., Dickens, B., Brown, W.E., Crystallographic studies of the role of Mg as a stabilizing impurity in β-Ca 3(PO 4) 2 - II. Refinement of Mg-containing β-Ca 3(PO 4) 2 (1977) J Sol State Chem, 22, pp. 253-262; Leadley, S.R., Davis, M.C., Ribeiro, C.C., Barbosa, M.A., Paul, A.J., Watts, J.F., Investigation of the dissolution of the bioceramic hydroxyapatite in the presence of titanium ions using ToF-SIMS and XPS (1997) Biomaterials, 18, pp. 311-316; Chusuei, C.C., Goodman, D.W., Van Stipdonk, M.J., Justes, D.R., Schweikert, E.A., Calcium phosphate phase identification using XPS and time-of-flight cluster SIMS (1999) Anal Chem, 71, pp. 149-153; Lu, H.B., Campbell, C.T., Graham, D.J., Ratner, B.D., Surface characterization of hydroxyapatite and related calcium phosphates by XPS and TOF-SIMS (2000) Anal Chem, 72, pp. 2886-2894; Tanahashi, M., Matsuda, T., Surface functional group dependence on apatite formation on self-assembled monolayers in a simulated body fluid (1997) J Biomed Mater Res, 34, pp. 305-315; Ma, Q.Y., Traina, S.J., Logan, T.J., Ryan, J.A., In situ lead immobilization by apatite (1993) Environ Sci Technol, 27, pp. 1803-1810; Xu, Y., Schwartz, F.W., Lead immobilization by hydroxyapatite in aqueous solutions (1994) J Contam Hydro, 15, pp. 187-206; Lower, S.K., Maurice, P.A., Traina, S.J., Carlson, E.H., Aqueous Pb sorption by hydroxylapatite: Applications of atomic force microscopy to dissolution, nucleation, and growth studies (1998) Am Miner, 83, pp. 147-158; Ribeiro, C.C., Barbosa, M.A., MacHado, A., Tudor, A., Davies, M.C., Modifications in the molecular structure of hydroxyapatite induced by Ti ions (1995) J Mater Sci: Mater Med, 6, pp. 829-834; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Fe 2+ and Fe 3+ ions (1990) J Chem Soc Faraday Trans, 86, pp. 1071-1075; Tanizawa, Y., Sawamura, K., Suzuki, T., Reaction characteristics of dental and synthetic apatites with Al 2+ and La 3+ ions in acidic solutions (1990) J Chem Soc Faraday Trans, 86, pp. 4025-4029; Layani, J.D., Mayer, I., Cuisinier, F.J.G., Carbonated hydroxyapatites precipitated in the presence of Ti (2000) J Inorg Biochem, 81, pp. 57-63; Gonzalez-Diaz, P.F., Santos, M., On the hydroxyl ions in apatites (1977) J Sol State Chem, 22, pp. 193-199; Vilchez, G.F., Griffith, W.P., Transition-metal tetra-oxo-complexes and their vibrational spectra (1972) J Chem Soc Dalton, 2, pp. 1416-1421; Bamberger, C.E., Begun, G.M., Cavin, O.B., Synthesis and characterization of sodium-titanium phosphates, Na 4(TiO)(PO 4) 2, Na(TiO)PO 4 and NaTi 2(PO 4) 3 (1988) J Solid State Chem, 73, pp. 317-324; El Jazouli, A., Krimi, S., Manoun, B., Chaminade, J.P., Gravereau, P., De Waal, D., Preparation and structural characterization of two new titanium phosphates NaCa 0.5Ti(PO 4) 3 and Ni 0.5TiOPO 4 (1998) Ann Chim Sci Mater, 23, pp. 7-10; Chernorukov, N.G., Korshunov, I.A., Zhuk, M.I., Hydro-ortho-derivatives of titanium of composition Ti(OH)PO 4 and Ti(OH)AsO 4 (1982) Russ J Inorg Chem, 27, pp. 1728-1731; Bamberger, C.E., Begun, G.M., Synthesis and characterisation of titanium phosphates, TiP 2O 7 and (TiO) 2P 2O 7 (1987) J Less Common Metals, 134, pp. 201-206
Keywords: article; Biocompatible Materials; concentration response; differential scanning calorimetry; drug mechanism; drug structure; Durapatite; Energy dispersive spectroscopy; Fourier transform infrared spectroscopy; hydroxyapatite; Incubation; infrared spectroscopy; Ions; Lattice constants; particulate matter; powder; Precipitation (chemical); priority journal; Solutions; Spectroscopy; Spectroscopy, Fourier Transform Infrared; temperature; Titanium; Titanium ions; Titanium phosphate; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

Adsorption isotherm of sodium ampicillin onto dense and porous hydroxyapatite - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2005)
The adsorption behaviour of sodium ampicillin to dense and porous hydroxyapatite as been extensively studied through the obtention of an adsorption isotherm. This isotherm was produced at body temperature, and a wide range of antibiotic solutions were used. The adsorption behaviour was measured by UV spectroscopy. The shape of the isotherm for the two forms of the material,dense and porous, indicates that the adsorption behaviour of the antibiotic seems to be different, however this is due to the adsorption taking place within the pores of the porous material, thus showing a larger amount of antibiotic adsorbed.
Keywords: Adsorption; Adsorption behavior; Adsorption isotherms; ampicillin; Antibiotics; hydroxyapatite; Porous hydroxyapatite; Porous materials; Sodium ampicillin; Sodium compounds; Ultraviolet spectroscopy

Assessment of the potential of Bonelike® graft for bone regeneration by using an animal model - Lobato, J.V.; Hussein, N.S.; Botelho, C.M.; Rodrigues, J.M.; Luís, A.L.; Maurício, A.C.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2005)
Bonelike® graft that mimics the inorganic composition of bone tissue has been developed and characterized over the last decade. To evaluate the osteoconductivity of Bonelike® two granule size ranges, one ranging from 150-250μm and the other from 250-500μm were implanted in the femurs of New Zealand White rabbits, aiming at being clinically used in different medical applications, such as dentistry and orthopaedics. In order to facilitate the medical application of the Bonelike® graft the use of a commercially available polymeric vehicle was also analyzed. Radiological examination, histological studies and scanning electron microscopy (SEM) analyses revealed that the surface of Bonelike® granules was almost completely surrounded by new bone formation after 12 weeks of implantation, which proves its highly osteoconductive behaviour.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Lobato, J.V.; ICBAS-Instituto de Ciências Biomédicas de Abel Salazar, Universidade do Porto, Largo Professor Abel Salazar 2, PT-4099-003 Porto, Portugal; email: jvlobato@netcabo.ptReferences: Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof European Patent WO 0068164Lopes, M.A., Santos, J.D., Monteiro, F.J., Push-out Testing and Histological Evaluation of Glass Reinforced Hydroxyapatite Composites Implanted in the Tibia of Rabbits (2001) J.Biomed Mater Res, 54, pp. 463-469;Lopes, M.A., Santos, J.D., Glass Reinforced Hydroxyapatite Composites; Secondary Phases Proportions and Densification Effects on Biaxial Bending Strength (1999) J.Biomed Mater Res, 48, pp. 734-740; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass Reinforced Hydroxyapatite Composites: Fracture Tougfiness and Hardness Dependence on Microstructural Characteristics (1999) Biomaterials, 2, pp. 2085-2090
Keywords: animal model; Animal models; Animals; Biomaterials; Biomedical engineering; Biomimetic materials; Bone; bone tissue; Bonelike graft; Bonelike® graft; Granular materials; In vivo studies; Scanning electron microscopy

Biocatalytic synthesis of highly ordered degradable dextran-based hydrogels - Ferreira, L.; Gil, M.H.; Cabrita, A.M.S.; Dordick, J.S. (BiomaterialsBiomaterials, 2005)
We have prepared unique macroporous and ordered dextran-based hydrogels using a single-step biocatalytic transesterification reaction between dextran and divinyladipate in neat dimethylsulfoxide. These hydrogels show a unimodal distribution of interconnected pores with average diameters from 0.4 to 2.0 μm depending on the degree of substitution. In addition, the hydrogels show a higher elastic modulus for a given swelling ratio than chemically synthesized dextran-based hydrogels. In vivo studies in rats show that the hydrogel networks are degradable over a range of time scales from 5 to over 40 days, and possess good biocompatibility, as reflected in only a mild inflammatory reaction and minor fibrous capsule formation during the time-frame of subcutaneous implantation. These combined properties may offer competitive advantages in biomedical applications ranging from tissue engineering to controlled drug delivery. © 2004 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2004.11.051PubMed ID: 15763250Language of Original Document: EnglishCorrespondence Address: Dordick, J.S.; Dept. of Chem. and Biol. Engineering, Rensselaer Polytechnic Institute, 102 Ricketts Bldg., Troy, NY 12180, United States; email: dordick@rpi.eduChemicals/CAS: dextran, 87915-38-6, 9014-78-2; dimethyl sulfoxide, 67-68-5; Biocompatible Materials; Dextrans, 9004-54-0; Hydrogels; Peptide Hydrolases, EC 3.4.-Manufacturers: Fluka, SwitzerlandReferences: Lee, K.Y., Peters, M.C., Anderson, K.W., Mooney, D.J., Controlled growth factor release from synthetic extracellular matrices (2000) Nature, 408, pp. 998-1000;Zhu, G., Mallery, S.R., Schwendeman, S.P., Stabilization of proteins encapsulated in injectable poly(lactide-co- glycolide) (2000) Nature Biotechnol, 18, pp. 52-57; Shea, L.D., Smiley, E., Bonadio, J., Mooney, D.J., DNA delivery from polymer matrices for tissue engineering (1999) Nature Biotechnol, 17, pp. 551-554; Griffith, L.G., Naughton, G., Tissue engineering-current challenges and expanding opportunities (2002) Science, 295, pp. 1009-1014; Lee, K.Y., Mooney, D.J., Hydrogels for tissue engineering (2001) Chem Rev, 101, pp. 1869-1879; Wong, W.H., Mooney, D.J., Synthesis and properties of biodegradable polymers used as synthetic matrices for tissue engineering (1997) Synthetic Biodegradable Polymer Scaffolds, pp. 49-82. , A. Atala D.J. Mooney Birkhäuser Boston; Holmes, T.C., Novel peptide-based biomaterial scaffolds for tissue engineering (2002) TIBTECH, 20, pp. 16-21; Mehvar, R., Dextrans for targeted and sustained delivery of therapeutic and imaging agents (2000) J Control Rel, 69, pp. 1-25; Kim, S.-H., Chu, C.-C., Synthesis and characterization of dextran-methacrylate hydrogels and structural study by SEM (2000) J Biomed Mater Res, 49, pp. 517-527; Kim, S.-H., Chu, C.-C., Pore structure analysis of swollen dextran-methacrylate hydrogels by SEM and mercury intrusion porosimetry (2000) J Biomed Mater Res (Appl Biomater), 53, pp. 258-266; Meyvis, T., De Smedt, S., Stubbe, B., Hennink, W., Demeester, J., On the release of proteins from degrading dextran methacrylate hydrogels and the correlation with the rheologic properties of the hydrogels (2001) Pharm Res, 18, pp. 1593-1599; Patil, N.S., Dordick, J.S., Rethwisch, D.G., Macroporous poly(sucrose acrylate) hydrogel for controlled release of macromolecules (1996) Biomaterials, 17, pp. 2343-2350; Park, H., Park, K., Biocompatibility issues of implantable drug delivery systems (1996) Pharm Res, 13, pp. 1770-1776; Loebsack, A., Greene, K., Wyatt, S., Culberson, C., Austin, C., Beiter, R., Roland, W., Halberstadt, C., In vivo characterization of a porous hydrogel material for use as a tissue bulking agent (2001) J Biomed Mater Res, 57, pp. 575-581; Cadée, J.A., Luyn, M.J.A., Brouwer, L.A., Plantinga, J.A., Van Wachem, P.B., Groot, C.J., Otter, W., Hennink, W.E., In vivo biocompatibility of dextran-based hydrogels (2000) J Biomed Mater Res, 50, pp. 397-404; Ferreira, L., Gil, M.H., Dordick, J.S., Enzymatic synthesis of dextran-containing hydrogels (2002) Biomaterials, 23, pp. 3957-3967; Washburn, E.W., Note on a method of determining the distribution of pore sizes in a porous material (1921) Proc Natl Acad Sci, 7, pp. 115-116; Brancroft, J.D., Stevens, A., (1996) Theory and Practice of Histological Techniques, , Churchill Livingstone Edinburgh; Martin, B.D., Linhardt, R.J., Dordick, J.S., Highly swelling hydrogels from ordered galactose-based polyacrylates (1998) Biomaterials, 19, pp. 69-76; Ferreira, L., Ramos, M.A., Gil, M.H., Dordick, J.S., Exquisite regioselectivity and transesterification activity enhancement of an immobilized Bacillus subtilis protease (2002) Biotechnol Prog, 18, pp. 986-993; Ferreira, L., Gil, M.H., Carvalho, R., Geraldes, C.F.G.C., Kim -., D.Y., Dordick, J.S., Biocatalytic polytransesterification of inulin with divinyladipate (2002) Chem Mater, 14, pp. 4009-4011; Zaks, A., Klibanov, A.M., Enzymatic catalysis in nonaqueous solvents (1988) J Biol Chem, 263, pp. 3194-3201; Almarsson, Ö., Klibanov, A.M., Remarkable activation of enzymes in nonaqueous media by denaturing organic cosolvents (1996) Biotechnol Bioeng, 49, pp. 87-92; Brøndsted, H., Hovgaard, L., Simonsen, L., Dextran hydrogels for colon-specific drug delivery II. Synthesis and characterization (1996) Eur J Pharm Biopharm, 42, pp. 85-89; De Smedt, S.C., Lauwers, A., Demeester, J., Van Steenbergen, M.J., Hennink, W.E., Roefs, S.P.F.M., Characterization of the network structure of dextran glycidyl methacrylate hydrogels by studying the rheological and swelling behavior (1995) Macromolecules, 28, pp. 5082-5088; Dziubla, I.D., Torjman, M.C., Joseph, J.I., Murphy-Tatum, M., Lowman, A.M., Evaluation of porous networks of poly(2-hydroxyethylmethacrylate) as interfacial drug delivery devices (2001) Biomaterials, 22, pp. 2893-2899; Kuijpers, A.J., Wachem, P.B., Luyn, M.J.A., Plantinga, J.A., Engbers, G.H.M., Krijgsveld, J., Zaat, S.A.J., Feijen, J., In vivo compatibility and degradation of crosslinked gelatin gels incorporated in knitted Dacron (2000) J Biomed Mater Res, 51, pp. 136-145; Suggs, L.J., Krishnan, R.S., Garcia, C.A., Peter, S.J., Anderson, J.M., Mikos, A.G., In vitro and in vivo degradation of poly(propylene fumarate-co-ethylene glycol) hydrogels (1998) J Biomed Mater Res, 42, pp. 312-320; Ferreira, L., Rafael, A., Lamghari, M., Barbosa, M.A., Gil, M.H., Cabrita, A.M.S., Dordick, J.S., Biocompatibility of chemoenzymatically derived dextran-acrylate hydrogels (2004) J Biomed Mater Res, 68, pp. 584-596; Van Dijk-Wolthuis, W.N.E., Hoogeboom, J.A.M., Van Steenbergen, M.J., Tsang, S.K.Y., Hennink, W.E., Degradation and release behavior of dextran-based hydrogels (1997) Macromolecules, 30, pp. 4639-4645
Keywords: Absorbable Implants; adipic acid derivative; animal experiment; animal tissue; Animals; article; Bacillus subtilis; Biocatalysts; Biocompatibility; Biocompatible Materials; Biodegradation; Biomedical engineering; biosynthesis; catalysis; Controlled drug delivery; controlled study; Cross-linking; dextran; Dextran-based hydrogels; Dextrans; dimethyl sulfoxide; Dimethylsulfoxide; Elastic moduli; Elasticity; Enzyme; Foreign-Body Reaction; hydrogel; Hydrogels; implantation; in vivo study; Inflammation; male; materials testing; nonhuman; Peptide Hydrolases; porosity; priority journal; rat; Rats; Rats, Wistar; substitution reaction; Sulfur compounds; Surface Properties; Swelling; Swelling ratio; synthesis; Tissue; transesterification; Transesterification reactions

Biological behaviour of Bonelike® graft implanted in the tibia of humans - Gutierres, M.; Hussain, N.S.; Afonso, A.; Almeida, L.; Cabral, T.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2005)
This paper reports the ability of Bonelike® to regenerate bone defected areas when implanted in the tibia of 3 patients (average age of 59 years) during a high tibial osteotomy (HTO) to treat medial compartment osteoarthritis of the knee. Bonelike® is a synthetic bone graft designed to mimic the inorganic composition of bone using a patent process that consists of liquid sintering hydroxyapatite in the presence of CaO-P 2O 5 based glass. The preliminary clinical evaluation performed showed that an intimate contact between new formed bone and Bonelike® was established (67±10%), with no fibrous interface. Therefore, Bonelike® is a single-handedly viable osteoconductive synthetic grafting material as it has been demonstrated from the profiles of radiological, histological and scanning electron microscopy analyses for the six months implantation period.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Gutierres, M.; Faculdade de Medicina da Universidade do Porto, Hospital de São João, Largo Hernâni Monteiro, 4200 Porto, Portugal; email: m.gutierres@clix.ptReferences: Bauer, T.W., Muschler, G.F., Bone Graft Materials. An Overview of the Basic Science (2000) Clin orthop Rel. Res, 371, pp. 10-27;Perry, C.R., Bone Repair Techniques, Bone Graft and Bone Graft Substitutes (1999) Clin Orthop Rel Res, 360, pp. 71-86; Ilan, D.I., Ladd, A.L., Bone graft substitutes (2003) Operative Tech. in plastic and Reconstructive Surgery, 9 (4), pp. 151-160; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof European Patent WO 0068164Lopes, M.A., Glass reinforced hydroxyapatite composites: Structural, Physicochemical characterisation and Biological performance (1999), PhD thesis, FEUP, University of Porto, PortugalCoventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J. Bone Joint Surg.Am, 47, p. 984; Lopes, M.A., Santos, J.D., (2001) J.Biomed Mat Res, 54, pp. 463-469
Keywords: Biological behavior; Bone; Bonelike® graft; Clinical trials; histology; hydroxyapatite; Implants (surgical); Radiology; Scanning electron microscopy; Surgery; Synthetic grafting material

Biological evaluation of calcium alginate microspheres as a vehicle for the localized delivery of a therapeutic enzyme - Barrias, C.C.; Lamghari, M.; Granja, P.L.; Sá Miranda, M.C.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Gaucher disease (GD) is caused by the decreased activity and/or stability of the lysosomal enzyme glucocerebrosidase (GCR). The available treatment consists in the intravenous administration of exogenous GCR, and is effective in reverting most of the symptoms. However, in terms of bone pathology, which is among the most disabling manifestations, a slow and incomplete response is observed, indicating that adjuvant therapies are necessary to consistently restore GCR activity in bone and accelerate regeneration. In this study, calcium alginate microspheres were analyzed as a vehicle for localized GCR delivery to bone. Results demonstrated that the entrapped enzyme retained full activity and exhibited a broader pH-dependent activity profile, compared to that of free-GCR, with improved stability at physiological pH. GCR release profile was established, and it was demonstrated that GCR could be released in a sustained manner. The biological behavior of the system was evaluated by analyzing the uptake of released GCR by GCR-deficient cells from GD patients, using different techniques: GCR activity measurements, radiolabeling, and cellulose acetate electrophoresis. Results demonstrated that GCR was internalized by cells significantly enhancing the residual enzymatic activity. To achieve an activity reconstitution level comparable to that obtained using free-GCR, only half of the dose was required with entrapped-GCR. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30348PubMed ID: 16028235Language of Original Document: EnglishCorrespondence Address: Barrias, C.C.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; calcium alginate, 9005-35-0; glucosylceramidase, 37228-64-1; iodine 125, 14158-31-7, 22822-81-7; Alginates; alginic acid, 9005-32-7; Drug Carriers; Enzymes, Immobilized; Glucosylceramidase, EC 3.2.1.45; Glucuronic Acid, 576-37-4; Hexuronic AcidsManufacturers: GenzymeReferences: Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev, 12, pp. 115-133;Zhao, H., Grabowski, G.A., Gaucher disease: Perspectives on a prototype lysosomal disease (2002) Cell Mol Life Sci, 59, pp. 694-707; Friedman, B., Vaddi, K., Preston, C., Mahon, E., Cataldo, J.R., McPherson, J.M., A comparison of the pharmacological properties of carbohydrate remodeled recombinant and placental-derived beta-glucocerebrosidase: Implications for clinical efficacy in treatment of Gaucher disease (1999) Blood, 93, pp. 2807-2816; Rasmussen, J., Barsomian, G., Bergh, M., Enzymatically active recombinant glucocerebrosidase. U.S. patent 6451600. 17 September 2002Elstein, D., Itzchaki, M., Mankin, H.J., Skeletal involvement in Gaucher's disease (1997) Baillieres Clin Haematol, 10, pp. 793-816; Wenstrup, R.J., Roca-Espiau, M., Weinreb, N.J., Bembi, B., Skeletal aspects of Gaucher disease: A review (2002) Br J Radiol, 75 (SUPPL. 1), pp. A2-A12; Mistry, P.K., Wraight, E.P., Cox, T.M., Therapeutic delivery of proteins to macrophages: Implications for treatment of Gaucher's disease (1996) Lancet, 348, pp. 1555-1559; Gregoriadis, G., Neerunjun, D., Meade, T.W., Goolamali, S.K., Weereratne, H., Bull, G., Experiences after long-term treatment of a type I Gaucher disease patient with liposome-entrapped glucocerebroside: Beta-glucosidase (1980) Birth Defects Orig Artic Ser, 16, pp. 383-392; Dale, G.L., Kuhl, W., Beutler, E., Incorporation of glucocerebrosidase into Gaucher's disease monocytes in vitro (1979) Proc Natl Acad Sci USA, 76, pp. 473-475; Beutler, E., Dale, G.L., Guinto, D.E., Kuhl, W., Enzyme replacement therapy in Gaucher's disease: Preliminary clinical trial of a new enzyme preparation (1977) Proc Natl Acad Sci USA, 74, pp. 4620-4623; Belchetz, P.E., Crawley, J.C., Braidman, I.P., Gregoriadis, G., Treatment of Gaucher's disease with liposome-entrapped glucocerebroside: Beta-glucosidase (1977) Lancet, 2, pp. 116-117; Korablyov, V., Zimran, A., Barenholz, Y., Cerebroside-beta-glucosidase encapsulation in liposomes for Gaucher's disease treatment revisited (1999) Pharm Res, 16, pp. 466-469; Busto, M.D., Ortega, N., Perez-Mateos, M., Effect of immobilization on the stability of bacterial and fungal beta-glucosidase (1997) Process Biochem, 32, pp. 441-449; Dashevsky, A., Protein loss by the microencapsulation of an enzyme (lactase) in alginate beads (1998) Int J Pharm, 161, pp. 1-5; Blandino, A., Macias, M., Cantero, D., Immobilization of glucose oxidase within calcium alginate gel capsules (2001) Process Biochem, 36, pp. 601-606; Kokufuta, E., Shimizu, N., Tanaka, H., Nakamura, I., Use of polyelectrolyte complex-stabilised calcium alginate gel for entrapment of beta-amylase (1988) Biotechnol Bioeng, 33, pp. 756-759; Edelman, E.R., Mathiowitz, E., Langer, R., Klagsbrun, M., Controlled and modulated release of basic fibroblast growth factor (1991) Biomaterials, 12, pp. 619-626; Peters, M.C., Isenberg, B.C., Rowley, J.A., Mooney, D.J., Release from alginate enhances the biological activity of vascular endothelial growth factor (1998) J Biomater Sci Polym Ed, 9, pp. 1267-1278; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Gagne, T.A., Chappell-Afonso, K., Johnson, J.L., McPherson, J.M., Oldham, C.A., Tubo, R.A., Vaccaro, C., Vasios, G.W., Enhanced proliferation and differentiation of human articular chondrocytes when seeded at low cell densities in alginate in vitro (2000) J Orthop Res, 18, pp. 882-890; (1993) Iodine-125. A Guide to Radioiodination Techniques: Amersham Life Science, , Amersham Place, Little Chalfont, Bucks: Amersham International pic; 64 pp; Sa Miranda, M.C., Aerts, J.M., Pinto, R., Fontes, A., De Lacerda, L.W., Van Weely, S., Barranger, J., Tager, J.M., Activity of glucocerebrosidase in extracts of different cell types from type 1 Gaucher disease patients (1990) Clin Genet, 38, pp. 218-227; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., Measurement of protein using bicinchoninic acid (1985) Anal Biochem, 150, pp. 76-85; Sa Miranda, M.C., Aerts, J.M., Pinto, R.A., Magalhaes, J.A., Barranger, J.A., Tager, J.M., Schram, A.W., Heterogeneity in human acid beta-glucosidase revealed by cellulose-acetate electrophoresis (1988) Biochim Biophys Acta, 965, pp. 163-168; Smidsrod, O., Draget, K.I., Chemistry and physical properties of alginates (1996) Carbohyd Eur, 14, pp. 6-13; Gaserod, O., Sannes, A., Skjak-Braek, G., Microcapsules of alginate-chitosan. II. A study of capsule stability and permeability (1999) Biomaterials, 20, pp. 773-783; Aslani, P., Kennedy, R.A., Studies on diffusion in alginate gels. I. Effect of cross-linking with calcium or zinc ions on diffusion of acetaminophen (1996) J Control Release, 42, pp. 75-82
Keywords: Alginates; alginic acid; article; Bone; bone disease; Bone Regeneration; Calcium alginate; Calcium Compounds; catalysis; Cell culture; Cells, Cultured; controlled study; Drug Carriers; drug delivery system; enzyme activity; enzyme assay; enzyme replacement; Enzymes; Enzymes, Immobilized; fibroblast culture; Fibroblasts; Gaucher disease; Gaucher disease (GD); Glucocerebrosidase (GCR); Glucosylceramidase; Glucuronic Acid; Hexuronic Acids; human; human cell; Humans; iodine 125; Localized delivery; lysosome enzyme; lysosome storage disease; microsphere; Microspheres; Pathology; pH effects; physiology; recombinant enzyme; Therapeutic enzyme

Bone substitutes: General concepts and "state of the art" - Gutierres, M.; Ascensão Lopes, M.; Sooraj Hussain, N.; Trigo Cabral, A.; Almeida, L.; Domingos Santos, J. (Substitutos ósseos: Conceitos gerais e estado actualArquivos de MedicinaArq. Med., 2005)
Bone grafts are nowadays the subject of extensive research worldwide, aimed at overcoming limitations associated with the use of autografts or bone banks to fill bone defects. Additionally, the use of osteogenic substances opens new perspectives in the treatment of fractures, pseudarthroses and vertebral arthrodeses. Due to the large amount of information available in the area of bone grafts, this paper aims not only to revise general concepts but also to summarize what has been published recently in the area of bone substitutes for bone regeneration. ©ArquiMed, 2006.
Keywords: Autografts; biomaterial; bone defect; bone demineralization; bone development; Bone graft; Bone growth factors; Bone morphogenetic protein; bone prosthesis; calcium phosphate; calcium sulfate; cortical bone; fibroblast growth factor; fracture; health care facility; health status; human; hydroxyapatite; platelet derived growth factor; pseudarthrosis; publication; review; somatomedin C derivative; spondylarthritis; transforming growth factor

Bonelike®/PLGA hybrid materials for bone regeneration: Preparation route and physicochemical characterisation - Oliveira, J.M.; Miyazaki, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Bonelike®/PLGA hybrid materials have been developed using γ-MPS as silane-coupling agent between the inorganic and organic phases for controlled drug delivery applications. Silanization showed to be more effective when cyclohexane was used as a non-polar solvent (nP method) due to a chemical interaction between Bonelike®, and the silane film, while by using a 95/5 (V/V) methanol/water as a polar solvent (P method), a much thinner film was achieved. Functional groups of PLGA, such as the carbonyl group (C=O), were identified using Raman and FTIR-ATR analysis and therefore these groups may be used to link therapeutic molecules. These novel hybrid materials prepared by combining silanization and post-hybridisation processes are expected to find use in medical applications of bone regeneration and as drug delivery carrier for therapeutic molecules. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-6687-yLanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; lactic acid, 113-21-3, 50-21-5; polyglycolic acid, 26124-68-5; cyclohexane, 110-82-7; methanol, 67-56-1; polyglactin, 26780-50-7, 34346-01-5; silane, 7803-62-5; water, 7732-18-5; Durapatite, 1306-06-5; Lactic Acid, 50-21-5; Polyglycolic Acid, 26009-03-0; polylactic acid-polyglycolic acid copolymer; Polymers; SilanesTradenames: Bonelike, AldrichManufacturers: AldrichReferences: Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , JAAS;Glimcher, M.J., (1976) Handbook of Physiology, Endocrinology, , edited by R. O. Greep and E. B. Astwood (American Physiological Society, Washington D.C.); Shors, E.C., Holmes, R.E., (1993) An Introduction to Bioceramics, p. 181. , edited by L. L. Hench and J. Wilson (World Scientific, Hong-Kong); Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 48, p. 734; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., (2000) Biomaterials, 21, p. 749; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905; Jha, L.J., Santos, J.D., Knowles, J.C., (1996) J. Biomed. Mater. Res., 31, p. 481; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci.: Mater. Med., 12, p. 629; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Wang, M., Deb, S., Bonfield, W., (2000) Mater. Lett., 44, p. 119; George, I., Viel, P., Bureau, C., Suski, J., Lécayon, G., (1996) Surf. Interf. Anal., 24, p. 774; Liu, Q., De Wijn, J.R., De Groot, K., Van Blitterwijk, C.A., (1998) Biomaterials, 19, p. 1067; Ara, M., Watanabe, M., Imai, Y., (2002) Biomaterials, 23, p. 2479; Agrawal, C.M., Ray, R.B., (2001) J. Biomed. Mater. Res., 55, p. 141; Arnold, U., Lindenhayn, K., Perka, C., (2002) Biomaterials, 23, p. 2303; Rizzi, S.C., Heath, D.J., Coombes, A.G.A., Bock, N., Textor, M., Downes, S., (2001) J. Biomed. Mater. Res., 55, p. 475; Simon Jr., C.G., Khatri, C.A., Wight, S.A., Wang, F.W., (2002) J. Orthop. Res., 20, p. 473; Mikos, A.G., Temenoff, J.S., (2000) EJB Electr. J. Biotechn., 3 (2); Laurencin, C.T., Attawia, M.A., Lu, L.Q., Borden, M.D., Lu, H.H., Gorum, W.J., Lieberman, J.R., (2001) Biomaterials, 22, p. 1271; Takenaga, M., Yamaguchi, Y., Kitagawa, A., Ogawa, Y., Mizushima, Y., Igarashi, R., (2002) J. Contr. Rel., 79, p. 81; Dupraz, A.M.P., De Wijn, J.R., Van De Meer, S.A.T., De Groot, K., (1996) J. Biomed. Mater. Res., 30, p. 231; Sheldon, R.P., (1982) Appl. Sci. Publ., 1, p. 1; Zhu, P.X., Ishikawa, M., Seo, W.S., Hozumi, A., Yokogawa, Y., Koumoto, K., (2002) J. Biomed. Mater. Res., 59, p. 294; Hooshmand, T., Van Noort, R., Keshvad, A., (2002) Dent. Mater., 18, p. 179; Venhoven, B.A.M., De Gee, A.J., Werner, A., Davidson, C.L., (1994) Biomaterials, 15, p. 1152; Yerby, S.A., Paal, A.F., Young, P.M., Beaupré, G.S., Ohashi, K.L., Goodman, S.B., (2000) J. Biomed. Mater. Res., 49, p. 127; Wang, M., Bonfield, W., (2001) Biomaterials, 22, p. 1311; Santos, C., Luklinska, Z.B., Clarke, R.L., Davy, K.W.M., (2001) J. Mater. Sci.: Mat. Med., 12, p. 565; Santos, J.D., Knowles, J.C., Hastings, G.W., in "Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof," European Patent No. WO0068164 (2000)Afonso, A., Santos, J.D., Vasconcelos, M., Branco, R., Cavalheiro, J., (1996) J. Mater. Sci.: Mater. Med., 7, p. 507; Hoffman, R., Westheim, J.G.F., Pouwel, I., Fransen, T., Gellings, P.J., (1996) Surf. Interf. Anal., 24, p. 1; Rider, A.N., Arnott, D.R., (1996) Surf. Interf. Anal., 24, p. 583; Eufinger, S., Van Ooij, W.J., Conners, K.D., (1996) Surf. Interf. Anal., 24, p. 841
Keywords: analytic method; article; Biological materials; Bone; Bone Regeneration; carbonyl derivative; chemical bond; chemical interaction; chemical reaction; Chemical reactions; chemistry; Chemistry, Physical; cyclohexane; Drug delivery; drug delivery system; Drug therapy; Durapatite; film; Fourier transform infrared spectroscopy; Hybrid materials; hybridization; hydroxyapatite; infrared spectroscopy; Lactic Acid; methanol; methodology; Microscopy, Electron, Scanning; Molecules; physical chemistry; polyglactin; polyglycolic acid; polylactic acid polyglycolic acid copolymer; polylactic acid-polyglycolic acid copolymer; polymer; Polymers; priority journal; Raman spectrometry; Raman spectroscopy; reaction analysis; Scanning electron microscopy; silane; silane derivative; Silanes; Silanization; solvent effect; Solvents; Spectroscopy, Fourier Transform Infrared; Spectrum Analysis, Raman; synthesis; Water; X ray; X-Rays

Characterization of fetal heart rate using approximate entropy - Marques De Sá, J.P. (Computers in CardiologyComput Cardiol, 2005)
Approximate entropy (ApEn) is an interesting measure for assessing the irregularity of time series and in particular for characterizing heart rate variability. In the present paper we apply ApEn to the characterization of three patterns of fetal heart rate (FHR): calm sleep; calm vigilance; pathological flat-sinusoidal condition. We conclude that ApEn can perfectly discriminate the pathological FS pattern from the normal A and C patterns and is far better for FHR pattern discrimination than classic time-domain variability indexes used in clinical practice. © 2005 IEEE.
Conference code: 69149Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusArt. No.: 1588190CODEN: COCADdoi: 10.1109/CIC.2005.1588190Language of Original Document: EnglishCorrespondence Address: Marques de Sá, J.P.; Faculdade de Engenharia, DEEC, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jmsa@fe.up.ptReferences: Felgueiras, C., Marques de, S.J., Bernardes, J., Gama, S., Classification of Foetal Heart Rate Sequences Based on Fractal Features (1998) Medical & Biological Engineering & Computing, 2, pp. 197-201;Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc. Natl. Acad. Sci. U.S.A, 88, pp. 2297-2301; Pincus, S.M., Viscarello, R.R., Approximate entropy: A regularity measure for fetal heart rate (1992) Obstet. Gynecol, 2, pp. 249-255; Pincus, S., Approximate Entropy (ApEn) as a Complexity Measure (1995) Chaos, 5, pp. 110-117; Pincus, S., Randomness and degrees of irregularity (1996) Proc. Natl. Acad. Sci. U.S.A, 93, pp. 2083-2088; Pincus, S., Kalman, R.E., Not all (possibly) "random" sequences are created equal (1997) Proc. Natl. Acad. Sci. U.S.A, 94, pp. 3513-3518; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin. Sci, 4, pp. 345-349; van Leeuwen, P., Lange, S., Betterman, H., Gronemeyer, D., Hatzmann, W., Fetal heart rate variability and complexity in the course of pregnancy (1999) Early Human Develop, 54, pp. 259-269; Pincus, S., Assessing Serial Irregularity and its Implications for Health (2001) Ann N Y Acad Sci, 954, pp. 245-267; Cysarz, D., Betterman, H., van Leeuwen, P., Entropies of short binary sequences in heart period dynamics (2000) Am J Physiol Heart Circ Physiol, 6, pp. 2163-2172; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J., Pereira-Leite, L., SisPorto 2.0 - A Program for Automated Analysis of Cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318
Keywords: Approximate entropy (ApEn); Cardiology; Fetal heart rate; Fetal monitoring; Heart rate variability; Pathology; Sleep research; Time domain analysis

Chemical modification of chitosan by phosphorylation: An XPS, FT-IR and SEM study - Amaral, I.F.; Granja, P.L.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2005)
In the present work, the surface of chitosan membranes was modified using a phosphorylation method carried out at room temperature. Phosphorylation may be of particular interest in materials for orthopaedic applications, due to the cation-exchange properties of phosphate functionalities. Phosphate groups chelate calcium ions, thus inducing the deposition of an apatite-like layer known to improve the osteoconduction of polymer-based implants. Additionally, the negatively charged phosphate functionalities, together with the positively charged amine groups from chitosan, are expected to provide chitosan with an amphoteric character, which may be useful as a combinatorial therapeutic strategy, by simultaneously allowing the immobilization of signalling molecules like growth factors. Phosphorylation was carried out at room temperature using the H 3 PO 4/Et 3 PO 4/P 2O 5/butanol method. Surface characterization was performed by XPS, ATR-FT-IR, and SEM. Cross-sections were analyzed by SEM fitted with EDS. The phosphate content increased with the reaction time, as shown by XPS and ATR-FT-IR, a P/N atomic ratio of 0.73 being obtained after 48 h of treatment. High-resolution XPS spectra regarding C 1s, O 1s, N 1s and P 2p are discussed. The introduction of a neutralization step led to a reduction of P content, which pointed out to the presence of phosphates ionically bound to protonated amines, in addition to phosphate esters. EDS analysis of cross-sections revealed a gradual P reduction up to 50% towards the inner part of the membrane. © VSP 2005.
Cited By (since 1996): 50Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856205774576736Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; phosphate, 14066-19-4, 14265-44-2; apatite, 64476-38-6; butanol, 35296-72-1, 71-36-3; calcium ion, 14127-61-8; Chitosan, 9012-76-4; PhosphatesReferences: Khor, E., (2001) Chitin: Fulfilling a Biomaterials Promise, , Elsevier Science, Oxford;Vande Vord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., (2002) J. Biomed. Mater. Res., 59, p. 585; Muzzarelli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., (1994) Biomaterials, 15, p. 1075; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J. Control. Rel., 78, p. 187; (2002) Chitosan in Pharmacy and Chemistry, p. 233. , R.A. A. Muzzarelli and C. Muzzarelli (Eds), in: Atec, Grottammare; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., (2002) Biomaterials, 23, p. 3227; Tanahashi, M., Matsuda, T., (1997) J. Biomed Mater. Res., 34, p. 305; Yokogawa, Y., Reyes, J.P., Mucalo, M.R., Toriyama, M., Kawamoto, Y., Suzuki, T., Nishizawa, K., Kamayama, T., (1997) J. Mater. Sci. Mater. Med., 8, p. 407; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., (1999) Biomaterials, 20, p. 879; Orban, J.M., Marra, K.G., Hollinger, J.O., (2002) Tissue Eng., 8, p. 529; Ilyina, A.V., Varlamov, V.P., Tikhonov, V.E., Yamskov, I.A., Davankov, V.A., (1994) Biotechnol. Appl. Biochem., 19, p. 199; Sugihara, J., Imamura, T., Yanase, T., Yamada, H., Imoto, T., (1982) J. Chromatogr., 229, p. 193; Kennedy, J.F., Cabral, J.M.S., (1983) Solid Phase Biochemistry: Analytical Synthetic Aspects, p. 253. , in: W. H. Schouten (Ed.) Wiley, New York, NY; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Granja, P.L., Pouysegu, L., Petraud, M., De Jeso, B., Baquey, C., Barbosa, M.A., (2001) J. Appl. Polym. Sci., 82, p. 3341; Fricain, J.C., Granja, P.L., Barbosa, A.M., de Jeso, B., Barthe, N., Baquey, C., (2002) Biomaterials, 23, p. 971; Sakairi, N., Shirai, A., Miyazaki, S., Tashiro, H., Tsuji, Y., Kawahara, H., Yoshida, T., Tokura, S., (1998) Kobunshi Ronbunshu, 55, p. 212; Sakaguchi, T., Horkoshi, T., Nakajima, A., (1981) Agricult. Biol. Chem., 45, p. 2191; Nishi, N., Ebina, A., Nishimura, S., Tsutsumi, A., Hasegawa, O., Tokura, S., (1986) Int. J. Biol. Macromol., 8, p. 311; Baxter, B., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., (1992) Int. J. Biol. Macromol., 14, p. 166; Wang, W., Bo, S.Q., Li, S.Q., Qin, W., (1991) Int. J. Biol. Macromol., 13, p. 281; Aiba, S., (1986) Int. J. Biol. Macromol., 8, p. 173; Hirano, S., Ohe, Y., Ono, H., (1976) Carbohydr. Res., 47, p. 315; Shigemasa, Y., Matsuura, H., Sashiwa, H., Saimoto, H., (1996) Int. J. Biol. Macromol., 18, p. 237; Seah, M.P., (1990) Practical Surface Analysis, 1, p. 541. , D.in: Briggs and M. P. Seah (Eds) Wiley, Chichester; Sherwood, P.M.A., (1990) Practical Surface Analysis, 1, p. 555. , in: D. Briggs and M. P. Seah (Eds) Wiley, Chichester; Hudson, S.M., Smith, C., (1998) Bio-polymers from Renewable Resources, p. 96. , in: D. L. Kaplan (Ed.) Springer, Berlin; Shepherd, R., Reader, S., Falshaw, A., (1997) Glycoconj. J., 14, p. 535; Wang, X.H., Ma, J.B., Wang, Y.N., He, B.L., (2001) Biomaterials, 22, p. 2247; Lee, Y.M., Shin, E.M., (1991) J. Membr. Sci., 64, p. 145; Kim, S.S., Jeong, W.Y., Shin, B.C., Oh, S.Y., Kim, H.W., Rhee, J.M., (1998) J. Biomed. Mater. Res., 40, p. 401; Whistler, R.L., Towle, G.A., (1969) Arch. Biochem. Biophys., 135, p. 396; Gardner, S.D., Singamsetty, C.S.K., Booth, G.L., He, G., (1995) Carbon, 33, p. 587; Briggs, D., (1990) Practical Surface Analysis, 1, p. 437. , in: D. Briggs and M. P. Seah (Eds) Wiley, Chichester; Beamson, G.D.B., (1992) High Resolution XPS of Organic Polymers, , Wiley, Chichester; Ratner, B.D., Caster, D.G., (1997) Surface Analysis - The Principal Techniques, p. 43. , in: J. C. Vickerman (Ed.) Wiley, Chichester; Bourbigot, S., Lebras, M., Gengembre, L., Delobel, R., (1994) Appl. Surf. Sci., 81, p. 299; Kilpadi, D.V., Raikar, G.N., Liu, J., Lemons, J.E., Vohra, Y., Gregory, J.C., (1998) J. Biomed. Mater. Res., 40, p. 646; Landis, W.J., (1984) Vac. Technol., A2, p. 1108; Wagner, C.D., Naumkin, A.V., Kraut-Vass, A., Alisson, J.W., Powell, C.J., Rumble Jr., J.R., (2003) NIST-X-ray Photoelectron Spectroscopy Database 20 Version 3.4, , http://srdata.nist.gov/xps/, National Institute of Standards and Technology, Gaithersburg, MD Available online at; Quan, D.T., Le Bloa, A., Habib, H., Bonnaud, O., Meinnel, J., Quemerais, A., Marchand, R., (1989) Rev. Phys. Appl., 24, p. 545; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interf. Sci., 95, p. 308; Domard, A., (1997) Advances in Chitin Science, 2, p. 410. , in: A. Domard, G. Roberts and K. Vårum (Eds) Jacques André, Lyon; Granja, P.L., Pouysegu, L., Deffieux, D., Daude, G., De Jeso, B., Labrugere, C., Baquey, C., Barbosa, M.A., (2001) J. Appl. Polym. Sci., 82, p. 3354; Roeges, N.P.G., (1994) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , Wiley, Chichester; Pearson, F.G., Marchessault, R.H., Liang, C.Y., (1960) J. Polym. Sci., 43, p. 101; Roberts, G.A.F., (1992) Chitin Chemistry, , Macmillan, London; Kuptsov, A.H., Zhizhin, G.N., (1998) Handbook of Fourrier Transform Raman and Infrared Spectra of Polymers, , Elsevier, Amsterdam; Daasch, L.W., Smith, D.C., (1951) Anal. Chem., 23, p. 854; Bueno, W.A., (1990) Manual De Espectroscopia Vibracional, , McGraw-Hill, São Paulo; Nyquist, R.A., Craver, C.D., (1997) The Coblentz Society Desk Book of Infrared Spectra, , The Coblentz Society, French Village, MO; Hirano, S., Tobetto, K., Noishiki, Y., (1981) J. Biomed. Mater. Res., 15, p. 903
Keywords: Acetylation; amine; animal; Animals; Apatite; article; bone conduction; butanol; calcium ion; cation exchange; cephalopod; chelate; Chemical modification; chemistry; Chitin; chitosan; comparative study; controlled study; Decapodiformes; Fourier transform infrared spectroscopy; Fourier transform infrared spectroscopy (FT-IR); Growth factor; immobilization; Implants (surgical); infrared spectroscopy; isolation and purification; Microscopy, Electron, Scanning; molecular weight; organophosphate; phosphate; Phosphate groups; Phosphates; Phosphorylation; Phosphorylation method; Plastics applications; priority journal; reflectometry; room temperature; Scanning electron microscopy; SEM-EDS; signal transduction; spectrometry; Spectrometry, X-Ray Emission; Spectroscopy, Fourier Transform Infrared; Surface chemical reaction; Surface Properties; surface property; temperature; time; Time Factors; viscosity; X ray photoelectron spectroscopy; X-rayphotoelectron spectroscopy (XPS)

Data parallel scheduling of operations in linear algebra on heterogeneous clusters - Morais, C.; Barbosa, J.; Tadeu, P. (WSEAS Transactions on ComputersWSEAS Trans. Comput., 2005)
The aim of data and task parallel scheduling for dense linear algebra kernels is to minimize the processing time of an application composed by several linear algebra kernels. The scheduling strategy presented here combines the task parallelism used when scheduling independent tasks and the data parallelism used for linear algebra kernels. This problem has been studied for scheduling independent tasks on homogeneous machines. Here it is proposed a methodology for heterogeneous clusters and it is shown that significant improvements can be achieved with this strategy.
Keywords: Computational complexity; Computer simulation; Heterogeneous clusters; Linear algebra; Mathematical models; Optimization; Parallel algorithms; Parallel processing systems; Parallel tasks; Static scheduling

Development of a system to adsorb drugs onto calcium phosphate materials - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Several studies were carried out in order to reduce the systemic use of antibiotics due to the high concentration required to provide the minimum inhibitory concentration (MIC) at infected sites. The aim of this study was to develop a system of drug adsorption onto commercial hydroxyapatite (HA, Ca 10(PO 4) 6(OH) 2) and glass reinforced hydroxyapatite (GR-HA) granules. The drug will then be released for the local treatment of periodontitis. The antibiotics used in this study were metronidazole, a specific antibiotic indicated for the systemic treatment of periodontitis, and ampicillin, a wide spectrum antibiotic. UV spectroscopy was used to measure the amount of drug adsorbed onto HA and GR-HA granules. Results showed that metronidazole was unable to adsorb on the material's surface, as opposed to ampicillin which adsorbed both onto HA and GR-HA. Preliminary release kinetics studies were carried out using a flow through dissolution system. Results are discussed in terms of the influence of the different surface characteristics of the materials on the adsorption processes. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-2535-3PubMed ID: 15965596Language of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: aqueiroz@ineb.up.ptChemicals/CAS: ampicillin, 69-52-3, 69-53-4, 7177-48-2, 74083-13-9, 94586-58-0; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; metronidazole, 39322-38-8, 443-48-1; Ampicillin, 69-53-4; Anti-Infective Agents; calcium phosphate, 10103-46-5; Calcium Phosphates; Coated Materials, Biocompatible; Delayed-Action Preparations; Drug Carriers; Metronidazole, 443-48-1References: Seymour, R.A., Heasman, P.A., Macgregor, I.D.M., (1992) Drugs, Diseases, and the Periodontium, 1. , edited by R. A. Seymour and P. A. Heasman Oxford University Press, Oxford;Carnevale, R.A., Greco, G.W., Bullard, C.M., Hanker, J.S., (1987) Biomedical Materials and Devices, p. 247. , edited by J. S. Hanker and B. L. Giammara Materials Research Society, Pittsburgh; Friedman, M., Steinberg, D., (1990) Pharm. Res., 7, p. 313; Hagiwara, S., Takamatsu, N., Tominaga, Y., Umeda, M., (1998) J. Period., 69, p. 62; Wright, T.L., Ellen, R.P., Lacroix, J.M., Sinnadurai, S., Mittelman, M.W., (1997) J. Period. Res., 32, p. 473; Golomb, G., Friedman, M., Soskolne, A., Stabholz, A., Sela, M.N., (1984) J. Dent. Res., 63, p. 1149; Goodson, J.M., Hogan, P.E., Dunham, S.L., (1984) J. Period., 55, p. 81; Somayaji, B.V., Jariwala, U., Jayachandran, P., Vidyalakshim, K., Dudhani, R.V., (1998) J. Period., 69, p. 409; Stoltze, K., (1992) J. Clin. Period., 19, p. 698; Goodson, J.M., Holborow, D., Dunn, R.L., Hogan, P., Dunham, S., (1983) J. Period., 54, p. 575; Yu, D., Wong, J., Matsuda, Y., Fox, J.L., Higuchi, W.I., Otsuka, M., (1992) J. Pharm. Sci., 81, p. 529; Nishihara, K., (1993) Clin. Mater., 12, p. 159; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 45, p. 376; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 47, p. 603; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mat. Res., 54, p. 463; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., (2001) Biomaterials, 22, p. 1393; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Knowles, J.C., Santos, J.D., Hastings, G.W., World Patent, WO0068164 (1994)Myers, H.M., Tochon-Danguy, H.J., Baud, C.A., (1983) Calcif. Tissue Int., 35, p. 745; Ratier, A., Gibson, I.R., Best, S.M., Freche, M., Lacout, J.L., Rodrigues, F., (2001) Biomaterials, 22, p. 897; Ando, D.J., (1996) Ultraviolet and Visible Spectroscopy, p. 16. , John Wiley & Sons, West Sussex
Keywords: Adsorption; ampicillin; Anti-Infective Agents; Antibiotics; article; Calcium Compounds; calcium phosphate; Calcium phosphates; Coated Materials, Biocompatible; concentration response; Delayed-Action Preparations; Diffusion; Dissolution; drug absorption; drug adsorption; Drug Carriers; Drug release; drug stability; glass; Glass reinforced hydroxyapatie (GR-HA); human; Humans; hydroxyapatite; Kinetics; Material's surface; Materials science; materials testing; metronidazole; minimum inhibitory concentration; Minimum inhibitory concentration (MIC); periodontitis; priority journal; Reaction kinetics; reduction; surface property; Ultraviolet spectroscopy

Effect of calcium phosphate addition to alginate microspheres: modulation of enzyme release kinetics and improvement of cell adhesion - Barrias, C.C.; Ribeiro, C.C.; Rodrigues, D.; Miranda, M.C.S.; Barbosa, M.A. (Key Engineering MaterialsKey Eng Mat, 2005)
In this study, the addition of calcium phosphate powders to an alginate matrix was evaluated as a strategy to modulate enzyme release-kinetics from alginate microspheres and, simultaneously, to improve cell adhesion to the polymer. Pre-adsorption of the enzyme to the ceramic powders resulted in a more adequate release pattern. The ratio of ceramic-to-polymer had a pronounced effect on osteoblast adhesion to microspheres. Cells were only able to spread on microspheres with the highest percentage of ceramic (0.4 w/w using a 1.5% w/v alginate solution).
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Barrias, C.C.; INEB - Institute de Engenharia Biomédica, Laboratório de Biomaterials, R. Campo Alegre 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptReferences: Graopwski, G.A., Leslie, N., Wenstrup, R., (1998) Blood Rev, 12, p. 115;Rowley, J.A., Madlambayan, G., Mooney, D.J., (1999) Biomaterials, 20, p. 45; Dalby, M.J., Di Silvio, L., Harper, E.J., Bonfield, W., (2002) Biomaterials, 23, p. 569
Keywords: Alginate; Bioceramics; calcium phosphate; Calcium titanium phosphate; cell adhesion; Enzyme kinetics; Enzyme release; hydroxyapatite; Microspheres; Osteoblasts

Feature extraction for classification of thin-layer chromatography images - Sousa, A.V.; Mendonça, A.M.; Campilho, A.; Aguiar, R.; Sá Miranda, C. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
Thin-Layer Chromatography images are used to detect and identify the presence of specific oligosaccharides, expressed by the existence, at different positions, of bands in the gel image. ID gaussian deconvolution, commonly used for band detection, does not produce good results due to the large curvature observed in the bands. To overcome this uncertainty on the band position, we propose a novel feature extraction methodology that allows an accurate modeling of curved bands. The features are used to classify the data into two different classes, to differentiate normal from pathologic cases. The paper presents the developed methodology together with the analysis and discussion of the results. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 67124Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/11559573_118Language of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Bajla, I., Holländer, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) M. S.R, 1 (1);Ye, X., Suen, C., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Vision Interface 99, , Canada; Shadle, S., Allen, D., Guo, H., Pogozelski, W., Bashkin, J., Tullius, T., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of aprotein-DNA binding constant (1997) Nucleic Acids Research, 25 (4); Sousa, A., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) Springer Lecture Notes on Computer Science, LNCS, 3212, pp. 372-380; Heijden, F., Duin, R., Ridder, D., Tax, D., (2004) Classification, Parameter Estimation and State Estimation, , John Wiley and Sons, England; Sewell, A., (1991) Urinary Oligosaccharides. Techniques in Diagnostic Human Biochemical Genetics, pp. 219-231. , Willey-Liss, Inc; Thomas, G., Disorders of Glycoprotein Degradation. α-Mahnosidosis, β-Mannosidosis, Fucosidosis and Sialidosis. Disorders of Glycoprotein Degradation, , Chap. 140; Durant, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clinical Chemistry, 46 (6), pp. 795-805; Marques De Sá, J., (2003) Applied Statistics Using SPSS, STATISTICA and MATLAD, , Springer Verlag
Keywords: Edge detection; Feature extraction; Image analysis; Image segmentation; Oligosaccharides; Thin layer chromatography; Thin-Layer Chromatography images

Genetic model-based segmentation of chest X-ray images using free form deformations - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
A method is proposed to segment digital posterior-anterior chest X-ray images. The segmentation is achieved through the registration of a deformable prior model, describing the anatomical structures of interest, to the X-ray image. The deformation of the model is performed using a deformation grid. A coarse matching of the model is done using anatomical landmarks automatically extracted from the image, and maps of oriented edges are used to guide the deformation process, optimized with a probabilistic genetic algorithm. The method is applied to extract the ribcage and delineate the mediastinum and diaphragms. The segmentation is needed for defining the lungs region, used in computer-aided diagnosis systems. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 67124Export Date: 21 November 2012Source: Scopusdoi: 10.1007/11559573_116Language of Original Document: EnglishCorrespondence Address: Vinhais, C.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinai e Imagem Biomédica, Campus da FEUP, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: cav@isep.ipp.ptReferences: Carreira, M., Cabello, D., Penedo, M., Mosquera, A., Computer-aided diagnoses: Automatic detection of lung nodules (1998) Medical Physics, 25 (10), pp. 1998-2006;Nakaromi, N., Doi, K., MacMahon, H., Sasaki, Y., Montner, S.M., Effect on heart-size parameters computed from digital chest radiographs on detection of cardiomegaly: Potencial usefulness for computer-aided diagnosis (1991) Inv. Radiology, 26, pp. 546-550; Van Ginneken, B., Romeny, B.H., Viergever, M.A., Computer-aided diagnosis in chest radiography: A survey (2001) IEEE Trans. on Medical Imaging, 20 (12), pp. 1228-1241; Cootes, T.E., Hill, A., Taylor, C.J., Haslam, J., The use of active shape models for locating structures in medical images (1994) Image, and Vision Computing, 12 (6), pp. 355-366; Sederberg, T.W., Parry, S.R., Free-form deformation of solid geometric models (1986) ACM SIGGRAPH Computer Graphics, 20 (4), pp. 151-160; Field, D.J., Relations between the statistics of natural images and the response properties of cortical cells (1987) J. Opt. Soc. Am. A, 4 (12), pp. 2379-2394; Petkov, N., Kruizinga, P., Computational models of visual neurons specialised in the detection of periodic and aperiodic oriented visual stimuli: Bar and grating cells (1997) Biol. Cybern., 76, pp. 83-96; Carpenter, M.B., (1991) Core Text of Neuroanatomy. 4th Ed.; Lotjonen, J., Magnin, I., Nenonen, J., Katila, T., Reconstruction of 3-D geometry using 2-D profiles and a geometric prior model (1999) IEEE Trans. on Medical Imaging, 18 (10), pp. 992-1002; Goldberg, D.E., (1989) Genetic Algorithms in Search, Optimization and Machine Learning; Gofman, Y., Kiryati, N., Detecting symmetry in grey level images: The global Optimization approach (1998) International Journal of Computer Vision (IJCV), 29, pp. 29-45
Keywords: Computer aided analysis; Diaphragms; Feature extraction; Free Form Deformation; Gabor Filters; Genetic Algorithms; Image segmentation; Model-based Image Segmentation; Optimization; Pattern matching; X ray analysis

Improving the adhesion of poly(ethylene terephthalate) fibers to poly(hydroxyethyl methacrylate) hydrogels by ozone treatment: Surface characterization and pull-out tests - Ferreira, L.; Evangelista, M.B.; Martins, M.C.L.; Granja, P.L.; Esteves, J.L.; Barbosa, M.A. (PolymerPolymer, 2005)
This work reports a methodology to improve the adhesion between poly(ethylene terephthalate) (PET) fibers and poly(hydroxyethyl methacrylate) (pHEMA) hydrogels by treating PET with ozone. The surface chemistry of PET was examined by water contact angle measurements, X-ray photoelectron spectroscopy (XPS), infrared reflection absorption spectroscopy (IRAS) and attenuated total reflectance infrared spectroscopy (ATR-IR) yielding information about the chemical functionalities at depths upon 0.6 μm. Ozone treatment introduces several polar groups in the surface of PET through oxidation and chain scission resulting in increased wettability. These groups include mostly carboxylic and anhydride groups and in small extent hydroxyl groups. Atomic force microscopy (AFM) analysis shows that the surface of ozone-treated PET films is fully covered with spherical particles that are removed after washing the film with water. During the washing step carboxylic functionalities were removed preferentially, as demonstrated by XPS and IR analysis. According to pull-out tests, PET monofilaments and bundles treated by ozone had a higher adhesion to pHEMA hydrogels than untreated ones. The apparent interfacial shear strength is 65% higher on pHEMA hydrogel containing an ozonated than an untreated PET monofilament. In addition, the force to pull-out an ozone-treated PET bundle from pHEMA hydrogel is ca. 81% higher than the one observed for the untreated bundle. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: POLMAdoi: 10.1016/j.polymer.2005.08.033Language of Original Document: EnglishCorrespondence Address: Ferreira, L.; Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: lino@mit.eduReferences: Hart, B.L., Deyo, R.A., Cherkin, D.C., (1995) Spine, 20, pp. 11-19;Bao, Q.-B., McCullen, G.M., Higham, P.A., Dumbleton, J.H., Yuan, H.A., (1996) Biomaterials, 17, pp. 1157-1167; Martz, E.O., Goel, V.K., Pope, M.H., Park, J.B., (1997) J Biomed Mater Res (Appl Biomater), 38, pp. 267-288; Strobel, M., Walzak, M.J., Hill, J.M., Lin, A., Karbashewski, E., Lyons, C.S., (1995) J Adhes Sci Technol, 9 (3), pp. 365-383; Le, Q.T., Pireaux, J.J., Caudano, R., (1997) J Adhes Sci Technol, 11, pp. 735-751; O'Hare, L.-A., Smith, J.A., Leadley, S.R., Parbhoo, B., Goodwin, A.J., Watts, J.F., (2002) Surf Interface Anal, 33, pp. 617-625; Walzak, M.J., Flynn, S., Foerch, R., Hil, J.M., Karbashewski, E., Lin, A., (1995) J Adhes Sci Technol, 9, pp. 1229-1248; Hill, J.M., Karbashewski, E., Lin, A., Strobel, M., Walzak, M.J., (1995) J Adhes Sci Technol, 9 (12), pp. 1575-1591; Blais, P., Day, M., Wiles, D.M., (1973) J Appl Polym Sci, 17, pp. 1895-1907; Day, M., Wiles, D.M., (1972) J Appl Polym Sci, 16, pp. 175-189; Nissen, K.E., Stevens, M.G., Stuart, B.H., Baker, A.T., (2001) J Polym Sci, Part B: Polym Phys, 39, pp. 623-633; Chen, W., McCarthy, T.J., (1998) Macromolecules, 31, pp. 3648-3655; Mougenot, P., Marchand-Brynaert, J., (1996) Macromolecules, 29, pp. 3552-3559; Hebeish, A., Shalaby, S.E., Bayazeed, A.M., (1981) J Appl Polym Sci, 26, pp. 3253-3269; Degert, C., Dupuy, B., Labat, B., Baquey, C., (1993) Biomat Art Cells Immobil Biotech, 21, pp. 553-561; Ambrosio, L., Netti, P.A., Iannace, S., Huang, S.J., Nicolais, L., (1996) J Mater Sci: Mater Int Med, 7, pp. 251-254; Rule, M., Physical constants of poly(oxyethylene-oxyterephthaloyl) (poly(ethylene terephthalate)) (1999) Polymer Handbook, pp. V/113-V/118. , J. Brandrup E.H. Immergut E.A. Grulke Wiley New York; Seah, M.P., Dench, W.A., (1979) Surf Interface Anal, 1, pp. 2-11; Strobel, M., Lyons, C., Strobel, J.M., Kapaun, R.S., (1992) J Adhes Sci Technol, 6 (4), pp. 429-443; Harrick, N.J., (1979) Internal Reflection Spectroscopy, , 2nd ed Wiley New York; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) The Contact Angle and Interface Energetics, , Plenum press New York; Peeling, J., Clark, D.T., (1983) J Polym Sci: Polym Chem Ed, 21, pp. 2047-2055; Peeling, J., Courval, G., Jazzar, M.S., (1984) J Polym Sci: Polym Chem Ed, 22, pp. 419-428; Razumovskii, S.D., Kefeli, A.A., Zaikov, G.E., (1971) Eur Polym J, 7, pp. 275-285; Wang, Y., Lehmann, S., (1999) Appl Spectrosc, 53, pp. 914-918; Liang, C.Y., Krimm, S., (1959) J Mol Spectrosc, 3, pp. 554-574; Pavia, D.L., Lampman, G.M., Kriz, G.S., (1996) Introduction to Spectroscopy, , 2nd ed Harcourt Brace College Publishers New York; Carlsson, D.J., Wiles, D.M., (1969) Macromolecules, 2 (6), pp. 597-606; Socrates, G., (2001) Infrared and Raman Characteristic Group Frequencies: Tables and Charts, , 3rd ed Wiley New York; Rabek, J.F., Lucki, J., Rånby, Y., Watanabe, Y., Qu, B.J., (1988) Photoozination of Polypropylene, , American Chemical Society Washington, DC; Ton-That, C., Teare, D.O.H., Campbell, P.A., Bradley, R.H., (1999) Surf Sci, 433-435, pp. 278-282; Tanaka, K., Minoshima, K., Grela, W., Komai, K., (2002) Compos Sci Technol, 62, pp. 2169-2177; Sadiku, E.R., Sanderson, R.D., (2001) Macromol Mater Eng, 286, pp. 535-545; Pisanova, E., Zhandarov, S., (2001) J Adhes, 75, pp. 89-127; Owens, D.K., (1975) J Appl Polym Sci, 19, pp. 3315-3326; Briggs, D., Rance, D.G., Kendall, C.R., Blythe, A.R., (1980) Polymer, 21, pp. 895-900; Fu, S.-Y., Yue, C.-Y., Hu, X., Mai, Y.-W., (2000) Compos Sci Technol, 60, pp. 569-579
Keywords: Adhesion; Atomic force microscopy; Contact angle; hydrogel; Hydrogels; infrared spectroscopy; Oxidation; Ozone; ozone treatment; Ozone treatments; Poly(ethylene terephthalate); polyethylene terephthalate fiber; Polyethylene terephthalates; Polymethyl methacrylates; pull-out; Pull-out tests; Surface characterization; Surface chemistry; surface property; X ray photoelectron spectroscopy

In situ thermal and structural characterization of bioactive calcium phosphate glass ceramics containing TiO 2 and MgO oxides: High temperature - XRD studies - Dias, A.G.; Skakle, J.M.S.; Gibson, I.R.; Lopes, M.A.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2005)
This study aims to develop glass ceramics in the calcium phosphate system that exhibit suitable properties to be used for biomedical applications. Calcium phosphate glasses with the incorporation of small additions of MgO and TiO 2 oxides were prepared in the pyro-and orthophosphate regions. The glass ceramics were prepared by a controlled powder sintering process through heat-treatment at different temperatures, as defined by results from differential thermal analysis (DTA). The composition of the crystalline phases precipitated in the glassy matrix as a result of heat treatments at different temperatures, ranging from 681 to 725 °C, was determined from X-ray diffraction data. The sequence of phase crystallization in the mother glass was also studied in situ using high temperature X-ray diffraction (HT-XRD) analysis. Results showed that the first phases that precipitated in the glass matrix were α- and β-Ca 2P 2O 7 at 620 °C. A small amount of CaTi 4(PO 4) 6 appeared at 630 °C. At 650 °C the three phases α-Ca 2P 2O 7, β-Ca 2P 2O 7 and CaTi 4(PO 4) 6 were clearly presented with a small amount of TiP 2O 7 and finally at 660 °C all four phases were observed. Glass ceramics were also characterized using Raman and X-ray photoelectron spectroscopy. This study demonstrates that, by altering the heat treatment cycle, it is possible to prepare glass ceramics in the calcium phosphate system that contains different bioactive and biocompatible phases. © 2005 Published by Elsevier B.V.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusCODEN: JNCSBdoi: 10.1016/j.jnoncrysol.2005.01.060Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Depto. De Engenharia Metalurgica E., Faculdade De Engenharia Da Univ. D., Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Franks, K., Abrahams, I., Georgiou, G., Knowles, J.C., (2001) Biomaterials, 22, p. 497;Rizkalla, A.S., Jones, D.W., Clarke, D.B., Hall, G.C., (1996) J. Biomed. Mater. Res., 32, p. 119; Navarro, M., Clément, J., Ginebra, M.P., Avila, G., Martínez, S., Planell, J.A., (2002) 17th European Society for Biomaterials Conference Proceedings, , Barcelona; Zhang, Y., Lopes, M.A., Santos, J.D., (2000) Bioceramics, 13, p. 643; Navarro, M., Clément, J., Ginebra, M.P., Martínez, S., Avila, G., Planell, J.A., (2002) Key Eng. Mater., 218-220, p. 275; Ohtsuki, C., Osaka, A., Kokubo, T., (1994) Bioceramics, 7, p. 73; Suzuki, T., Toriyama, M., Hosono, H., Abe, Y., (1991) J. Ferment. Bioeng., 72, p. 384; Abe, Y., Hosono, H., Hosoe, M., (1987) Phosphorus Sulfur, 30, p. 337; Schneider, K., Heimann, R.B., Berger, G., (2001) Werkstofftech., 32, p. 166; Lin, F.H., Lin, C.C., Lu, C.M., (1995) Biomaterials, 16, p. 793; Lin, C.C., Liao, C.J., Sun, J.S., (1996) Biomaterials, 17, p. 1133; Dias, A.G., Tsuru, K., Hayakawa, S., Lopes, M.A., Santos, J.D., Osaka, A., (2004) Glass Technol., 45, p. 78; Bish, D.L., Howard, S.A., (1988) J. Appl. Cryst., 21, p. 86; De Fátima Gimenez, I., Mazali, I.O., Alves, O.L., (2001) J. Phys. Chem. Solids, 62, p. 1251; Krimi, S., Eljazouli, A., Rabardel, L., Couzi, M., Mansouri, I., Leflem, G., (1993) J. Solid State Chem., 102, p. 400; Barj, M., Lucazeau, G., Delmas, C., (1992) J. Solid State Chem., 100, p. 141; NIST Standard Reference Database; Shih, P.Y., Yung, S.W., Chin, T.S., (1998) J. Non-Cryst. Solids, 224, p. 143; Reaney, I.M., James, P.F., Lee, W.E., (1996) J. Am. Ceram. Soc., 79, p. 1934; Ryu, H.-S., Youn, H.-J., Chang, B.-S., Lee, C.-K., Chung, S.-S., (2002) Biomaterials, 23, p. 909; Kitsugi, T., Yamamuro, T., Nakamura, T., Oka, M., (1995) Biomaterials, 16, p. 1101; Dias, A.G., Costa, M.A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Eng. Mater., 254-256, p. 825; Bian, J.J., Kim, D.W., Hong, K.S., (2003) J. Eur. Ceram. Soc., 23 (14), p. 2589; Clarck, T.J., Reed, J.S., (1986) J. Am. Ceram. Soc., 69, p. 837; Siligardi, C., D'Arrigo, M.C., Leonelli, C., (2000) Am. Ceram. Soc. Bull., p. 88; Chowdari, V.R., Subba Rao, G.V., Lee, G.Y.H., (2000) Solid State Ionics, 136-137, p. 1067
Keywords: Biocompatibility; Calcium Compounds; Calcium phosphate systems; Cavity fillers; Computer software; Crystallinity; Differential thermal analysis; Fourier transform infrared spectroscopy; Glass ceramics; Magnesia; Phase analysis; Raman spectroscopy; Titanium dioxide; X ray diffraction analysis; X ray photoelectron spectroscopy

In vitro analysis of protein adhesion to phase pure hydroxyapatite and silicon substituted hydroxyapatite - Botelho, C.M.; Brooks, R.A.; Kawai, T.; Ogata, S.; Ohtsuki, C.; Best, S.M.; Lopes, M.A.; Santos, J.D.; Rushton, N.; Bonfield, W. (Key Engineering MaterialsKey Eng Mat, 2005)
The adhesion of bovine collagen type I, bovine serum albumin, bovine IgG, 1 % and 10 % (v/v) human serum to hydroxyapatite (HA), silicon-substituted hydroxyapatite (Si-HA) and tissue culture plastic were studied. The materials were incubated at 37°C for 30 minutes, after which the protein solution was removed and analyzed. The adsorbed protein was evaluated by electrophoresis and immunoassay after extraction from the materials. The degree of adhesion was higher for collagen, followed by IgG and albumin on all materials. However there was no difference in the amount of collagen adsorbed onto the surface of each material and this was also the finding with albumin and IgG. These results suggest that the increased bioactivity seen with Si-HA is not due to the degree of protein adhesion, but may possibly be due to changes in the conformation of the bound proteins.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Botelho, C.M.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ccunha@fe.up.ptReferences: Patel et al, J. of Mat. Sci.: Mat. in Med., 13 (2002) p. 1199Gibson, I.R., (1999) Bioceramics, 12, p. 191;Botelho, C.M., in Key (2003) Engineering Materials, 254-256, pp. 841-844; Porter, (2004) Biomaterials, 5, pp. 3303-3314; Takami et al, in J. Biomed Mater. Res., 40, (1998), p. 24-30Kandori, (2004) in J. Colloid and Interface Science, 273, pp. 406-413; Vermeer, (2001) Biochimicaet Biophysica Acta, 1526, pp. 61-69; Kikuchi, (2001) Biomaterials, 22, pp. 1705-1711; Jha, L.J., Worldwide patent, PCT/GB97/02325 and US Patent Serial (1999), No 09/147773Gibson, I.R., (1999) J. Biomed. Mat. Res, 44, p. 422; Botelho, C.M., (2002) J. Mater. Sci:Mater. Med, 13, pp. 1123-1127; Muller, (1999) Macromol. Rapid Commun, 20, pp. 607-611; Veerman, (1987) Biomaterials, 8, pp. 442-448; Haynes, in Colloids and Surfaces B (1994) Biointerfaces, 2, pp. 517-566; Reffit, D.M., (2003) Bone, 32, p. 127
Keywords: Adsorption; Bioactivity; Bovine collagen type I; Bovine collagens; Bovine serum proteins; Collagen; Human serum proteins; hydroxyapatite; Immunoglobulin G (IgG); immunology; Silicon-substituted hydroxyapatite; Substitution reactions; Tissue culture

In vitro biodegradability of chitosan-organosiloxane hybrid membrane - Tsuru, K.; Shirosaki, Y.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandas, M.H. (Key Engineering MaterialsKey Eng Mat, 2005)
Chitosan-silicate hybrid membranes were prepared using γ- glycidoxypropyltrimethoxysilane (GPSM) through a sol-gel process. The amino groups of chitosan chains were reacted with the epoxy groups of GPSM and GPSM have a function as the agent to cross-link the chitosan chains. The cross-linking degree of the hybrid membranes was determined by ninhydrin assay. Fourier-transform infrared (FT-IR) spectroscopy and 29Si cross-polarization (CP) magic-angle spinning (MAS)-NMR spectroscopy were used to assess the structure of the hybrid membranes. The biodegradability of the hybrid membranes in phosphate-buffered saline solution or lysozyme solution was investigated as a function of the GPSM concentration.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Tsuru, K.; Faculty of Engineering, Biomaterial Laboratory, Okayama University, Tsushima, Okayama 700-8530, Japan; email: kanji@cc.okayama-u.ac.jpReferences: Chandy, T., Sharma, P.C., (1990) Biomat Art Cells Art Org, 18, pp. 1-24;Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., (2001) J Ceram Soc Japan, 109, pp. 403-408; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., (2002) Biomaterials, 23, pp. 4765-4773; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Engineering Materials, 254-256, pp. 857-860; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, pp. 485-493; S. Prochazkova, K. M. Vårum, K. Østgaard, Carbohydrate Polymers, 38 (1999), p. 115-122Brinker, J.C., Scherer, G.W., (1989) Sol-Gel Science, The Physics and Chemistry of Sol-Gel Processing, , Academic Press, San Diego
Keywords: biodegradability; Biological membranes; chitosan; Chitosan chains; Chitosan inorganic hybrid membranes; Chitosan-lnorganlc hybrid; Crosslinking; Fourier transform infrared spectroscopy; Nuclear magnetic resonance spectroscopy; R- glycidoxypropyltrimethoxysilane GPSM; Reaction kinetics; Silicates; Sol-gel process

In vitro cytocompatibility of MG63 cells on chitosan-organosiloxane hybrid membranes - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2005)
Chitosan-silicate hybrids were synthesized using γ- glycidoxypropyltrimethoxysilane (GPSM) as the agent for cross-linking the chitosan chains. CaCl 2 was introduced in the hybrids in expectation that it would improve cell adhesion and differentiation of the hybrid surfaces. Fourier-transform infrared (FT-IR) spectroscopy and 29Si CP-MAS NMR spectroscopy were used to analyze the structures of the hybrids. Cytocompatibility of the hybrids was investigated in terms of proliferation of an osteoblastic cell line, MG63. The adhesion and proliferation of the osteoblastic cells cultured on the surface of a chitosan-GPSM hybrid without calcium were similar to those on a control culture plate, and were better than those on a chitosan membrane. The ALP activity of the cells cultured on this hybrid was higher than that on the chitosan membrane. Contrary to expectations, the incorporation of calcium ions into the hybrids did not improve cell attachment and proliferation on their surfaces. © 2004 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 55Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2004.02.056PubMed ID: 15276356Language of Original Document: EnglishCorrespondence Address: Hayakawa, S.; Biomaterial Laboratory, Faculty of Engineering, Okayama Univ., 3-1-1 T., Okayama-shi, Japan; email: satoshi@cc.okayama-u.ac.jpChemicals/CAS: calcium chloride, 10043-52-4; Alkaline Phosphatase, EC 3.1.3.1; Biocompatible Materials; Calcium, 7440-70-2; Chitosan, 9012-76-4; Cross-Linking Reagents; gamma-glycidoxypropyltrimethoxysilane, 2530-83-8; Membranes, Artificial; Neoplasm Proteins; SilanesManufacturers: Chisso, Japan; Kasei, JapanReferences: Park, J.B., Lakes, R.S., (1992) Biomaterials An Introduction, pp. 223-234. , New York: Plenum Press;Wise, D.L., (2000) Biomaterials and Bioengineering Handbook, pp. 556-559. , New York: Marcel Dekker; Lee, Y.K., Mooney, J.D., Hydrogels for tissue engineering (2001) Chem Rev, 101, pp. 1869-1879; Park, S.N., Park, J.C., Kim, H.O., Song, M.J., Suh, H., Characterization of porous collagen/hyaluronic acid scaffold modified by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide cross-linking (2002) Biomaterials, 23, pp. 1205-1212; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering: Part 1 Structure, gelation rate and mechanical properties (2001) Biomaterials, 22, pp. 511-521; Widmer, M.S., Gupta, P.K., Lu, L., Meszlenyi, R.K., Evans, G.R.D., Brandt, K., Savel, T., Mikos, A.G., Manufacture of porous biodegradable polymer conduits by an extrusion process for guided tissue regeneration (1998) Biomaterials, 19, pp. 1945-1955; Wang, Y.C., Lin, M.C., Wang, D.M., Hsieh, H.J., Fabrication of a novel porous PGA-chitosan hybrid matrix for tissue engineering (2003) Biomaterials, 24, pp. 1047-1057; Domard, A., Rinaudo, M., Preparation and characterization of fully deacetylated chitosan (1983) Int J Biol Macromol, 5, pp. 49-52; Chandy, T., Sharma, P.C., Chitosan - As a biomaterial (1990) Biomater Artif Cells Artif Organo, 18, pp. 1-24; Ueno, H., Yamada, H., Tanaka, I., Kaba, N., Matsuura, M., Okumura, M., Kadosawa, T., Fujinaga, T., Accelerating effects of chitosan for healing at early phase of experimental open wound in dogs (1999) Biomaterials, 20, pp. 1407-1414; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., Porous calcium phosphate coating over phosphorylated chitosan film by a biomimetic method (1999) Biomaterials, 20, pp. 879-884; Xiao, C., Gao, S., Wang, H., Zhang, L., Blend films from chitosan and konjac glucomannan solutions (2000) J Appl Polym Sci, 76, pp. 509-515; Chung, T.W., Lu, Y.F., Wang, S.S., Lin, Y.S., Chu, S.H., Growth of human endothelial cells on photochemically grafted Gly-Arg-Gly-Asp (GRGD) chitosans (2002) Biomaterials, 23, pp. 4803-4809; Muzzareli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., Stimulatory effect on bone formation exerted by a modified chitosan (1994) Biomaterials, 15, pp. 1075-1081; Park, Y.J., Lee, M.Y., Lee, J.Y., Seol, Y.J., Chung, C.P., Lee, S.J., Controlled release of platelet-derived growth factor-BB from chondroitin sulfate-chitosan sponge for guided bone regeneration (2000) J Controlled Rel, 67, pp. 385-394; Suzuki, T., Mizushima, Y., Umeda, T., Ohashi, R., Further biocompatibility testing of silica-chitosan complex membrane in the production of tissue plasminogen activator by epithelial and fibroblast cells (1999) J Biosci Bioeng, 88, pp. 194-199; Yamaguchi, I., Itoh, S., Suzuki, M., Sakane, M., Osaka, A., Tanaka, J., The chitosan prepared from crab tendon I: The characterization and the mechanical properties (2003) Biomaterials, 24, pp. 2031-2036; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Controlled Rel, 78, pp. 187-197; Kawamura, Y., Mitsuhashi, M., Tanibe, H., Yoshida, H., Adsorption of metal ions on polyaminated highly porous chelating resin (1993) Ing Eng Chem Res, 32, pp. 386-391; Jameela, S.R., Jayakrishnan, A., Glutaraldehyde crosslinked chitosan as a long acting biodegradable drug delivery vehicle: Studies on the in vitro release of mitoxantrone and in vivo degradation of microspheres in rat muscle (1995) Biomaterials, 16, pp. 769-775; Speer, D.P., Chvapil, M., Eskelson, C.D., Ulreich, J., Biological effects of residual glutaraldehyde in glutaraldehyde-tanned collagen biomaterials (1980) J Biomed Mater Res, 14, pp. 753-764; Nishi, C., Nakajima, N., Ikada, Y., In vitro evaluation of cytotoxicity of diepoxy compounds used for biomaterial modification (1995) J Biomed Mater Res, 29, pp. 829-834; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Sol-gel preparation and in vitro deposition of apatite on porous gelatin-siloxane hybrids (2001) J Non-Cryst Solid, 285, pp. 116-122; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Novel approach to fabricate porous gelatin-siloxane hybrids for bone tissue engineering (2002) Biomaterials, 23, pp. 4765-4773; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2- yl)-2,5-diphenyltetrazolium bromide (MTT) subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Ren, L., Tsuru, K., Hayakawa, S., Osaka, A., Incorporation of Ca 2+ ions in gelatin-siloxane hybrids through a sol-gel process (2001) J Ceramic Soc Japan, 109, pp. 403-408; Yamaguchi, I., Tokuchi, K., Fukuzaki, H., Koyama, Y., Takakuda, K., Monma, H., Tanaka, J., Preparation and microstructure analysis of chitosan/hydroxyapatite nanocomposites (2001) J Biomed Mater Res, 55, pp. 20-27; Hench, L.L., Ethridge, E.C., (1982) Biomaterias An Interfacial Approach, p. 10. , New York: Academic Press; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., Osteoblasts: Differentiation and function (1993) Handbook of Experimental Pharmacology, pp. 149-183. , J.R. Mundy, & T.J. Martin. Berlin: Springer; Aubin, J.E., Turksen, K., Heersch, J.N.M., Osteoblastic cell lineage (1993) Cellular and Molecular Biology of Bone, pp. 1-45. , M. Noda. Tokyo: Academic Press Inc; Anderson, S.I., Downes, S., Perry, C.C., Caballero, A.M., Evaluation of the osteoblast response to a silica gel in vitro (1998) J Mater Sci: Mater Med, 9, pp. 731-735; Rhee, S.H., Hwang, M., Si, H.J., Choi, J.Y., Biological activities of osteoblasts on poly(methyl methacrylate)/silica hybrid containing calcium salt (2003) Biomaterials, 24, pp. 901-906; Kalonji, E.E., Denis, I., Lieberherr, M., Pointillart, A., Effects of extracellular calcium on the proliferation and differentiation of porcine osteoblasts in vitro (1998) Cell Tissue Res, 292, pp. 163-171; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma-sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Bilezikian, J.P., Raisz, L.G., Rodan, G.A., (2002) Principles of Bone Biology, p. 1325. , New York: Academic Press
Keywords: alkaline phosphatase; article; artificial membrane; Biocompatibility; Biocompatible Materials; Bone Neoplasms; Calcium; calcium chloride; cell adhesion; Cell attachments; Cell culture; cell differentiation; Cell Division; Cell Line, Tumor; chitosan; chitosan derivative; controlled study; cross linking; Cross-Linking Reagents; Crosslinking; Cytocompatibility; Fourier transform infrared spectroscopy; human; human cell; Humans; hybrid; infrared spectroscopy; Magnetic Resonance Spectroscopy; materials testing; Membranes, Artificial; MG63 osteoblastic cells; Microscopy, Electron, Scanning; Neoplasm Proteins; Nuclear magnetic resonance spectroscopy; Organic-inorganic hybrid; osteoblast; Osteoblasts; Osteosarcoma; priority journal; Silanes; Silicates; siloxane; Spectroscopy, Fourier Transform Infrared; structure analysis; surface property; Synthesis (chemical); wettability; γ-Glycidoxypropyltrimethoxysilane (GPSM)

In vitro degradation behavior of a novel bioresorbable composite material based on PLA and a soluble CaP glass - Navarro, M.; Ginebra, M.P.; Planell, J.A.; Barrias, C.C.; Barbosa, M.A. (Acta BiomaterialiaActa Biomater., 2005)
Poly(α-hydroxy acids), and in particular polylactic acid (PLA), are nowadays amongst the most used bioabsorbable materials. However, this polymer may not meet some application requirements due to inadequate mechanical properties and or its degradation characteristics. A possible strategy to tackle this problem is the incorporation of an inorganic phase into the polymeric matrix. In this work a new fully biodegradable composite material made with PLA and calcium phosphate soluble glass particles has been developed. The behaviour of the PLA/ glass composite has been analysed during its degradation in simulated physiological conditions by means of weight loss, molecular weight and thermal properties analysis and electron microscopy observation. The results showed that the incorporation of phosphate glass particles into the polymer significantly accelerated the degradation of the PLA and induced the formation of calcium phosphate precipitates at the composite surface. © 2005 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Cited By (since 1996): 24Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2005.03.004PubMed ID: 16701822Language of Original Document: EnglishCorrespondence Address: Ginebra, M.P.; Reference Centre for Bioengineering of Catalonia (CREBEC), Department of Materials Science, Universitat Politècnica de Catalunya, Av. Diagonal 647, 08028 Barcelona, Spain; email: maria.pau.ginebra@upc.esChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; polylactic acid, 26100-51-6; Bone Substitutes; calcium phosphate, 10103-46-5; Calcium Phosphates; Lactic Acid, 50-21-5; poly(lactic acid), 26100-51-6; PolymersManufacturers: Purac, NetherlandsReferences: Rokkanen, P., Bioabsorbable fixation in orthopaedic surgery and traumatology (2000) Biomaterials, 21, pp. 2607-2613;Middleton, J.C., Tipton, A.J., Synthetic biodegradable polymers as orthopedic devices (2000) Biomaterials, 21 (23), pp. 2335-2346; Adriano, K.P., Daniels, A.U., Smutz, W.P., Wyatt, R.W.B., Heller, J., Preliminary biocompatibility screening of several biodegradable phosphate fiber reinforced polymers (1993) J Appl Biomater, 4, pp. 1-12; Nazhat, S.N., Kellomaki, M., Tormala, P., Tanner, K.E., Bonfield, W., Dynamic mechanical characterization of biodegradable composites of hydroxyapatite and polylactides (2001) J Biomed Mater Res, 58 (4), pp. 335-343; Dupraz, A.M.P., de Wijn, J.R., v.d. Meer, S.A.T., de Groot, K., Characterization of silane-treated hydroxyapatite powders for use as filler in biodegradable composites (1996) J Biomed Mater Res, 30, pp. 231-238; Kasuga, T., Maeda, H., Kato, K., Nogami, M., Hata, K.-I., Ueda, M., Preparation of poly (lactic acid) composites containing calcium carbonate (vaterite) (2003) Biomaterials, 24, pp. 3247-3253; Ylinen, P., Suuronen, R., Taurio, R., Tormala, P., Rokkanen, P., Use of hydroxylapatite/polymer-composite in facial bone augmentation. An experimental study (2002) Int J Oral Maxillofac Surg, 31 (4), pp. 405-409; Lu, H.H., El-Amin, S., Scott, K., Laurencin, C., Three-dimensional, bioactive, biodegradable, polymer-bioactive glass composite scaffolds with improved mechanical properties support collagen synthesis and mineralization of human osteoblast-like cells in vitro (2003) J Biomed Mater Res, 64 A, pp. 465-474; Navarro, M., Ginebra, M.P., Planell, J.A., Zeppetelli, S., Ambrosio, L., Development and cell response of a new biodegradable composite scaffold for guided bone regeneration (2004) J Mater Sci-Mater Med, 15 (4), pp. 419-422; Klein, C.P.A.T., Driessen, A.A., Degroot, K., Vandenhooff, A., Biodegradation behavior of various calcium-phosphate materials in bone tissue (1983) J Biomed Mater Res, 17 (5), pp. 769-784; Denissen, H.W., Degroot, K., Makkes, P.C., Vandenhooff, A., Klopper, P.J., Tissue-response to dense apatite implants in rats (1980) J Biomed Mater Res, 14 (6), pp. 713-721; Navarro, M., Ginebra, M.P., Clement, J., Martinez, S., Avila, G., Planell, J.A., Physicochemical degradation of titania-stabilized soluble phosphate glasses for medical applications (2003) J Am Ceram Soc, 86 (8), pp. 1345-1352; Navarro, M., Ginebra, M.P., Planell, J.A., Cellular response to calcium phosphate glasses with controlled solubility (2003) J Biomed Mater Res Part A, 67 A (3), pp. 1009-1015; Li, S.M., Hydrolytic degradation characteristics of aliphatic polyesters derived from lactic and glycolic acids (1999) J Biomed Mater Res, 48 (3), pp. 342-353; Burg, K.J.L., Shalaby, S.W., Physicochemical changes in degrading polylactide films (1997) J Biomat Sci Polym, 9 (1), pp. 15-29; Li, S.M., Vert, M., Hydrolytic degradation of coral/poly(DL-lactic acid) bioresorbable material (1996) J Biomat Sci-Polym, 7 (9), pp. 817-827; Agrawal, C.M., Athanasiou, K.A., Technique to control pH in vicinity of biodegrading PLA-PGA implants (1997) J Biomed Mater Res, 38 (2), pp. 105-114; Kokubo, T., Kushitani, H., Sakka, S., Kitsugi, T., Yamamuro, T., Solutions able to reproduce invivo surface-structure changes in bioactive glass-ceramic A-W3 (1990) J Biomed Mater Res, 24 (6), pp. 721-734; Fischer, E.W., Sterzel, H.J., Wegner, G., Investigation of the structure of solution grown crystals of lactide copolymers by means of chemical reactions (1973) Kolloid-Zeitschrift and Z Polymere, 251, pp. 978-990; Driessens, F.C.M., Fernandez, E., Ginebra, M.P., Boltong, M.G., Planell, J.A., Calcium phosphates and ceramic bone cements vs. acrylic cements (1997) Anales Quimica, 93 (1), pp. S38-S43; Berry, E.E., Baddiel, C.B., Some assignments in infra-red spectrum of octacalcium phosphate (1967) Spectrochim Acta Part A - Mol Spectrosc A, 23 (6), p. 1781; Fowler, B.O., Moreno, E.C., Brown, W.E., Infra-red spectra of hydroxyapatite octacalcium phosphate and pyrolysed octacalcium phosphate (1966) Arch Oral Biol, 11 (5), p. 477; Elliot, J.C., General chemistry of the calcium orthophosphates. Structure and chemistry of the apatites and other calcium orthophosphates (1994), pp. 1-61. , Elsevier AmsterdamStutman, J.M., Termine, J.D., Posner, A.S., Vibrational spectra and structure of phosphate ion in some calcium phosphates (1965) Trans New York Acad Sci, 27 (6), p. 669; Cornilsen, B.C., Condrate, R.A., The vibrational spectra of β-Ca 2P 2 O 7 and γ-Ca 2P 2O 7 (1979) J Inorg Nucl Chem, 41, pp. 602-605; Cornilsen, B.C., Condrate, R.A., Vibrational spectra of α-alkaline earth pyrophosphates (1978) J Solid State Chem, 23, pp. 375-382; de Fátima Gimenez, I., Mazali, I.O., Alves, O.L., Application of Raman spectroscopy to the study of the phase composition of phosphate based glass-ceramics (2001) J Phys Chem Solids, 62, pp. 1251-1255; Kasuga, T., Abe, Y., Calcium phosphate invert glasses with soda and titania (1999) J Non-Cryst Solids, 243, pp. 70-74; Imai, Y., Fukuzawa, A., Watanabe, M., Effect of blending tricalcium phosphate on hydrolytic degradation of a block polyester containing poly(L-lactic acid) segment (1999) J Biomat Sci - Polym, 10 (7), pp. 773-786; Huffman, K.R., Casey, D.J., Effect of carboxyl end groups on hydrolysis of polyglycolic acid (1985) J Polym Sci Part A - Polym Chem, 23 (7), pp. 1939-1954; Termine, J.D., Eanes, E.D., Comparative chemistry of amorphous and apatitic calcium phosphate preparations (1972) Calcif Tissue Res, 10 (3), p. 171; Zahidi, E., Lebugle, A., Bonel, G., On a new class of biomaterials for osseous or dental prosthesis (1985) Bull Soc Chim France, (4), pp. 523-527; Eanes, E.D., Gillesse, I.H., Gosner, A.S., Intermediate states in precipitation of hydroxyapatite (1965) Nature, 208 (5008), p. 365; Tung, M.S., Brown, W.E., An intermediate state in hydrolysis of amorphous calcium-phosphate (1983) Calcif Tissue Int, 35 (6), pp. 783-790; Wuthier, R.E., Rice, G.S., Wallace, J.E.B., Weaver, R.L., Legeros, R.Z., Eanes, E.D., Invitro precipitation of calcium-phosphate under intracellular conditions - Formation of brushite from an amorphous precursor in the absence of Atp (1985) Calcif Tissue Int, 37 (4), pp. 401-410; Root, M.J., Inhibition of the amorphous calcium-phosphate phase-transformation reaction by polyphosphates and metal-ions (1990) Calcif Tissue Int, 47 (2), pp. 112-116;
Keywords: Absorbable Implants; Absorption; article; biodegradability; Biodegradable composite; Biomimetic materials; Body fluids; Bone Regeneration; Bone Substitutes; calcium phosphate; Calcium phosphates; composite material; Degradation; electron microscopy; glass; In vitro degradation; in vitro study; Lactic Acid; materials testing; molecular weight; observation; Phosphate glass; polylactic acid; Polymers; precipitation; priority journal; reaction analysis; simulation; Solubility; Surface Properties; surface property; temperature; weight reduction

In vitro studies of calcium phosphate glass ceramics with different solubility with the use of human bone marrow cells - Dias, A.G.; Lopes, M.A.; Trigo Cabral, A.T.; Santos, J.D.; Fernandes, M.H. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Two glass ceramics in the CaO-P 2O 5-MgO system with the incorporation of K 2O or TiO 2 oxides were prepared with the goal of using them as potential bone graft substitutes. The incorporation of TiO 2 and K 2O led to the preparation of specific crystalline phases in the structure of the glass ceramics, which show different degrees of biodegradation. In fact, the 45CaO-45P 2O 5-5MgO-5K 2O has been previously demonstrated to be much more soluble in aqueous solutions than the 45CaO-37P 2O 5-5MgO-13TiO 2 glass ceramic. The in vitro biological activity of the two calcium phosphate glass ceramics was studied with the use of human bone marrow osteoblast cell cultures maintained for 28 days, and seeded materials were assessed for cell proliferation and function. The Ti-containing glass ceramic showed a stable surface throughout the culture time, on macroscopic and SEM observation. Osteoblast cells proliferated gradually, especially during the third week, with a high alkaline phosphatase activity and formation of a mineralized matrix. On SEM observation, attached cells appeared with a spreadpolygonal morphology typical of the osteoblast cells, with extensive cell-to-cell contact. Cell behavior on the seeded material was similar to that found on cultures performed on tissue-culture-grade polystyrene; except for the presence of lower cell numbers during the first 2 weeks. By contrast, the K-containing glass ceramic showed a highly instable surface with dissolution/precipitation processes occurring throughout the culture time. Few cells adhered to the material surface, and subsequent proliferation was also hindered, especially from the first week onwards. Cell numbers were significantly lower than those observed in the Ti-containing glass ceramic during most of the incubation time. Results suggest that the different in vitro biological behavior of these two glass ceramics is mainly due to the significant differences in the surface degradation rate, which is directly correlated to the chemical composition of the mother glass. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30357PubMed ID: 15988737Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; FMDUP-Faculdade de Medicina Dentária da Universidade do Porto, Rua Dr. Manuel Pereira da Silva, 4200 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; polystyrene, 9003-53-6; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; Alkaline Phosphatase, EC 3.1.3.1; calcium phosphate, 10103-46-5; Calcium Phosphates; Ceramics; Glass ceramics, 85422-94-2References: Yaszemski, M.J., Payne, R.G., Hayes, W.C., Langer, R., Mikos, A.C., Evolution of bone transplantation: Molecular, cellular and tissue strategies to engineer human bone (1996) Biomaterials, 17, pp. 175-185;Rueger, J.M., Bone replacement materials-state of the art and the way ahead (1998) Orthopade, 27, pp. 72-79; Tadic, D., Epple, M., A thorough physicochemical characterization of 14 calcium phosphate-based bone substitution materials in comparison to natural bone (2004) Biomaterials, 25, pp. 987-994; Greenwald, A.C., Bolden, S.D., Goldberg, V.M., Khan, Y., Laurencin, C.T., Rosier, R.N., Bone-graft substitutes: Facts, fictions and applications (2001) J Bone Joint Surg, 83 A, pp. 98-103; Damien, C.J., Parson, J.R., Bone graft and bone graft substitutes: A review of current technology and applications (1997) J Appl Biomater, 2, pp. 187-208; Lettuec, J.C., Clément, D., Lesprit, E., Faber, J., The use of calcium phosphates, their biological properties (2000) Eur J Orthop Surg Traumatol, 10, pp. 223-229; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angew Chem Int Ed Engl, 41, pp. 3130-3146; Dias, A.G., Lopes, M.A., Gibson, I.R., Santos, J.D., In vitro degradation studies of calcium phosphate glass ceramics prepared by controlled crystallization (2003) J Non-Cryst Solids, 330, pp. 81-89; Fini, M., Giardino, R., In vitro and in vivo tests for the biological evaluation of candidate orthopedic materials: Benefits and limits (2003) J Appl Biomater Biomech, 1, pp. 155-163; Hunt, J.A., McLaughlin, P.J., Flanagan, B.F., Review-Techniques to investigate cellular and molecular interaction in the host response to implanted biomaterials (1997) Biomaterials, 18, pp. 1449-1459; Dias, A.G., Tsuru, K., Hayakawa, S., Lopes, M.A., Santos, J.D., Osaka, A., Crystallization studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications (2004) Glass Technol, 45; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; Kumari, T.V., Vasudev, U., Kumar, A., Menon, B., Cell surface interactions in the study of biocompatibility (2002) Trends Biomater Artif Organs, 15, pp. 37-41; Sun, J.S., Tsuang, Y.H., Liao, C.J., Liu, H.C., Hang, Y.S., Lin, F.H., The effects of calcium phosphate particles on the growth of osteoblasts (1997) J Biomed Mater Res, 37, pp. 324-334; Sun, J.S., Whs, C., Chen, L.T., Huang, Y.C., Juang, L.W., Lin, F.H., The influence on gene-expression profiling of osteoblasts behavior following treatment with the ionic products of sintered β-dicalcium pyrophosphate dissolution (2004) Biomaterials, 25, pp. 607-616; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: Effect of ascorbic acid b-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Morais, S., Dias, N., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions (1999) J Biomed Mater Res, 44, pp. 176-190; Coelho, M.J., Cabral, A.T., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in alpha-MEM and in DMEM (2000) Biomaterials, pp. 211087-211094; Dias, A.G., Lopes, A.G., Santos, J.D., Fernandes, N.H., The influence of pre-incubation treatment in the in vitro biological performance of degradable CaO-P 2O 5 glass ceramics (2005) Key Eng Mater, 284-286, pp. 565-568; Bitar, M., Salih, V., Mudera, V., Knowles, J.C., Lewis, M.P., Soluble phosphate glasses: In vitro studies using human cells of hard and soft tissue origin (2004) Biomaterials, 25, pp. 2283-2292; Suzuki, T., Yamamoto, T., Toriyana, M., Nishizawa, K., Yokogawa, Y., Mucalo, M.R., Kawamoto, Y., Kameyama, T., Surface instability of calcium phosphate ceramics in tissue growth of anchorage-dependent animal cells (1997) J Biomed Mater Res, 34, pp. 507-517; Ducheyne, P., Qiu, Q., Bioactive ceramics: The effect of surface reactivity on bone formation and bone cell function (1999) Biomaterials, 20, pp. 2287-2303; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Mineral, 14, pp. 27-40; Stein, G.S., Lian, J.B., Stein, J.L., Van Wijnen, A.J., Frenkel, B., Montecino, M., Mechanism regulating osteoblast proliferation and differentiation (1996) Principles of Bone Biology, pp. 69-83. , Bilezikian JP, Raisz LG, Rodan GA, editors. New York: Academic Press; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., Biodegradation study of potassium calcium metaphosphate in the SBF and Tris-buffer solution (2002) Key Eng Mater, 218-220, pp. 149-152; Ploska, U., Berger, G., Solubility of compositions in the system CaTi xZr 4 - X(PO 4) 6 with x = 0-4 (1997) Biomaterials, 18, pp. 1671-1675; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., In situ thermal and structural characterization of bioactive calcium phosphate glass ceramics containing TiO 2 and MgO oxides: HT-XRD studies (2005) J Non-Cryst Solids, , Forthcoming; Chun, S., Jeong, J.H., Kim, K.H., Kim, S., Biodegradation study of amorphous and crystalline calcium metaphosphate in SBF and Tris-buffer solution (2001) Key Eng Mater, 192-195, pp. 131-134; Elghannam, A., Ducheyne, P., Shapiro, I.M., Bioactive material template for in vitro synthesis of bone (1995) J Biomed Mater Res, 29, pp. 359-370; Kitsugi, T.T., Yamamuro, T., Nakamura, T., Oka, M., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorous molar ratios (1995) Biomaterials, 16, pp. 1101-1107; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue response in the femur of rabbits after implantation of a new calcium titanium phosphate composition (2001) Key Eng Mater, 192-195, pp. 383-386; Hill, P.A., Orth, M., Bone remodeling - Review (1998) Br J Orthod, 25, pp. 101-107
Keywords: alkaline phosphatase; aqueous solution; article; Biodegradation; Bone; Bone graft; bone marrow cell; Bone Marrow Cells; bone mineralization; bone prosthesis; Calcium Compounds; calcium phosphate; Calcium phosphate glass ceramic; Calcium phosphate glass ceramics; Calcium phosphates; cell contact; Cell culture; cell proliferation; Cells; ceramics; chemical composition; controlled study; crystal structure; Dissolution; enzyme activity; extracellular matrix; glass; Glass ceramics; human; Human bone marrow cells; human cell; Humans; in vitro study; In vitro testing; Magnesia; magnesium derivative; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; polystyrene; Precipitation (chemical); Scanning electron microscopy; Solubility; Spectrum Analysis; Surface treatment; Titanium dioxide

Inflammatory cell recruitment and adhesion to methyl-terminated self-assembled monolayers: Effect of implantation time - Barbosa, J.N.; Barbosa, M.A.; Águas, A.P. (Microscopy Research and TechniqueMicrosc. Res. Tech., 2005)
The contribution of methyl groups in implant-triggered inflammation was investigated in vivo using self-assembled monolayers (SAMs) of alkanethiols on gold. The CH 3-coated implants were inserted in an air-pouch cavity induced in BALB/c mice. The in situ inflammatory response was monitored 24, 48, and 72 hours later. Inflammatory cells recovered from the air pouches were counted and observed by light microscopy. The cellularity of the implant surfaces was defined by scanning electron microscopy (SEM). In comparison with gold implants, the CH 3-coated SAMs recruited a significantly higher number of inflammatory cells. Polymorphonuclear leukocytes (PMN) were more numerous than mononuclear cells (Mo) in the exudates recovered from the air pouches with CH 3-coated SAMs. The opposite PMN/Mo proportion was observed in air pouches of the two control groups (mice receiving gold implants or sham-operated animals). A low density of adherent cells was seen on CH 3-coated implants, with no significant quantitative differences during the time course of the study. In contrast, the gold-coated surfaces were covered with numerous cells during all of the 3 days of the inflammation. In conclusion, implants with CH 3 surfaces are likely to induce PMN-dominated local acute inflammation but these surfaces are not associated with a significant adherence of leukocytes to the implant. © 2005 Wiley-Liss, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: MRTEEdoi: 10.1002/jemt.20141PubMed ID: 15816035Language of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB, Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; thiol derivative, 13940-21-1; Coated Materials, Biocompatible; Gold, 7440-57-5References: Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110;Babensee, J.E., Anderson, J.M., Mclntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliv Rev, 33, pp. 111-139; Barbosa, J.N., Barbosa, M.A., Águas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold (2004) Biomaterials, 25, pp. 2557-2563; Castro, A.G., Esaguy, N., Macedo, P.M., Águas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Gelb, H., Schumacher, H.R., Cuckler, J., Ducheyne, P., Baker, D.G., In vivo inflammatory response to polymethylmethacrylate particulate debris: Effect of size, morphology, and surface area (1994) J Orthop Res, 12, pp. 83-92; Hooper, K.A., Nickolas, T.L., Yurkow, E.J., Kohn, J., Laskin, D., Characterization of the inflammatory response to biomaterials using a rodent air pouch model (2000) J Biomed Mater Res, 50, pp. 365-374; Hu, W., Eaton, J.W., Tang, L., Molecular basis of biomaterial-mediated foreign body reactions (2001) Blood, 98, pp. 1231-1238; Isaji, M., Momose, Y., Naito, J., Enhancement of inflammatory reactions in a non-immunological air pouch model in rats (1989) Br J Exp Pathol, 70, pp. 705-716; Källtorp, M., Oblogina, S., Jacobsson, S., Karlsson, A., Tengvall, P., Thomsen, P., In vivo cell recruitment, cytokine release and chemiluminescence response at gold, and thiol functionalized surfaces (1999) Biomaterials, 20, pp. 2123-2137; Kao, W.J., Evaluation of leukocyte adhesion on polyurethanes: The effects of shear stress and blood proteins (2000) Biomaterials, 21, pp. 2295-2303; Kao, W.J., Liu, Y., Gundloori, R., Li, J., Lee, D., Einerson, N., Burmania, J., Stevens, K., Engineering endogenous inflammatory cells as delivery vehicles (2002) J Control Release, 78, pp. 219-233; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkane thiols on gols surfaces (1997) Biomaterials, 18, pp. 1059-1068; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on cibacron blue F3G-A immobilized onto oligo(ethylene glycol)-terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14, pp. 945-954; Mrksich, M., Using self-assembled monolayers to understand the biomaterials interface (1997) Curr Opin Colloid Int Sci, 2, pp. 83-88; Mrkisich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Mrksich, M., Whitesides, G.M., Interactions of SAMs with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiences for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Prime, K.L., Whitesides, G.M., Self assembled organic monolayers: Model systems for studying the adsorption of proteins at surfaces (1991) Science, 252, pp. 1164-1167; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Tang, L., Eaton, J.W., Mechanisms of acute inflammatory response to biomaterials (1994) Cells and Materials, 4, pp. 429-436; Tang, L., Eaton, J.W., Inflammatory responses to biomaterials (1995) Am J Clin Pathol, 103, pp. 466-471; Tang, L., Ugarova, T.P., Plow, E.F., Eaton, J.W., Molecular determinants of acute inflammatory responses to biomaterials (1997) J Clin Invest, 97, pp. 1329-1334; Tang, L., Jennings, T.A., Eaton, J.W., Mast cells mediate acute inflammatory responses to implanted biomaterials (1998) Proc Natl Acad Sci, 95, pp. 8841-8846; Tang, L., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Tomczok, J., Sliwa-Tomczok, W., Klein, C.L., Van Kooten, T.G., Kirkpatrick, C.J., Biomaterial-induced alterations of human neutrophils under fluid shear stress: Scanning electron microscopical study in vitro (1996) Biomaterials, 17, pp. 1359-1367; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Wooley, P.H., Mayton, L., Sud, S., Nasser, S., Synergistic inflammatory responses to metallic and polymeric particles in the murine air pouch model of aseptic loosening (1996) Arthritis Rheum, 39, pp. 175-183; Wooley, P.H., Morren, R., Andary, J., Sud, S., Yang, S., Mayton, L., Markel, D., Nasser, S., Inflammatory responses to orthopaedic biomaterials in the murine air pouch (2002) Biomaterials, 23, pp. 517-526; Yun, J.K., DeFife, K., Colton, E., Stack, S., Azeez, A., Cahalan, L., Verhoeven, M., Anderson, J.M., Human monocyte/macrophage adhesion and cytokine production on surface-modified poly (tetrafluoroethylene/hexafluoropropylene) polymers with and without protein preadsorption (1995) J Biomed Mater Res, 29, pp. 257-268
Keywords: Air-pouch model; animal experiment; animal model; Animalia; Animals; article; biomaterial; cell adhesion; Cell Count; cell density; cell surface; Cell-surface interactions; Coated Materials, Biocompatible; Contact angle; controlled study; gold; implantation; Implants, Experimental; Inflammation; inflammatory cell; Inflammatory responses; leukocyte adherence; Leukocytes; male; materials testing; methyl group; Mice; Microscopy, Electron, Scanning; mononuclear cell; mouse; neutrophil; nonhuman; priority journal; Scanning electron microscopy; Self-assembled monolayers; Surface Properties; thiol derivative; Time Factors

The influence of pre-incubation treatment in the in vitro biological performance of degradable CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2005)
Based upon the CaO-P 2O 5 glass system, two glass ceramics were prepared in the meta-, pyro- and orthophosphate regions. The present work describes results concerning the biological activity of MT13B (45CaO-37P 2O 5-5MgO-13TiO 2, in mol %) and MK5B (45CaO-45P 2O 5-5MgO-5K 2O, in mol %) using MG63 osteoblast-like cells cultured for 6 days. The influence of a 24h pretreatment with culture medium before cell culture was also evaluated (MT13Bi; MK5Bi). Both "as-received" and pre-treated material samples supported cell growth, which increased with the culture time. Pre-treatment resulted in an increase of adhered cells on both materials (day 1). Throughout the culture time (days 3 and 6), MT13Bi presented higher cell numbers than that of MT13B, but no differences were found between MK5Bi and MK5B. In addition, cell growth was significantly lower in the K-containing glass ceramic in both experimental situations comparing with Ti-containing glass ceramic. SEM and confocal microscopy observation showed that cell adhesion and spreading were hampered on MK5B samples. Evident macroscopic and microscopic surface instability was observed on this material with simultaneous dissolution/precipitation processes. By contrast, MT13B presented a relatively stable surface throughout the culture time. Results suggest that the pre-incubation with culture medium improves the adhesion of the osteoblast cells to both glass ceramics and that the high degradation rate of MK5B hinders the in vitro biological performance of this material.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Dias, A.G.; FEUP-Faculdade de Engenharia, Universidade do Porto, DEMM, Rua Dr. Roberta Frias, 4200 Porto, Portugal; email: pde99423@fe.up.ptReferences: Damien, C.J., Bone graft and bone graft substitutes a review of current technology and applications (1997) Journal of Applied Biomaterial, 2, pp. 187-208;Dias, A.G., In vitro degradation studies of calcium phosphate glass ceramics prepared by controlled crystallization (2003) Journal of Non-Crystalline Solids, 330 (1-3), pp. 81-89; Dias, A.G., Crystallization studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications (2004) Glass Technology, 45 (2), pp. 78-79; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681
Keywords: Bioactivity; biodegradability; Biodegradable glass ceramics; Calcium Compounds; Cell culture; cell growth; Glass ceramics; MG63 osteoblast-like cells; Orthophosphate; Osteoblasts; Pretreatment

A method for simultaneously precipitating and dispersing nano-sized calcium phosphate suspensions - Lemos, A.F.; Rebelo, A.H.S.; Rocha, J.H.G.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2005)
Stable and relatively concentrated aqueous suspensions of nano-sized stoichiometric hydroxyapatite could be prepared by a precipitation method in the presence of suitable surface active agent (SAA). The method includes the precipitation, vacuum filtration and washing of the precipitated powders, followed by re-dispersion. It could be concluded that the added amount of the SAA should be enough to cover the primary particles surface, and that washing should be better carried out using a SAA solution. The method developed enables the precipitation of the powders and the preparation of suspensions, while significantly shortening the overall time required for colloidal processing consuming.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Lemos, A.F.; Ceramic and Glass Engineering Department, Campus de Santiago, University of Aveiro, 3810-193 Aveiro, Portugal; email: ilemos@cv.ua.ptReferences: de Groot, K., (1983) Bioceramics of Calcium Phosphates, , CRC Press, Boca Raton, FL;Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, , World Scientific, London, UK; Liu, H.S., Chin, T.S., Lai, L.S., Chiu, S.Y., Chung, K.H., Chang, C.S., Lui, M.T., (1997) Ceramics International, 23, p. 19; Zhang, S., Gonsalves, K.E., (1997) J. Mater. Sci.: Mater. Med, 8, p. 25; Takeo, H., Yasuhiko, I., Hiroshi, I., (1987) J. Ceram. Soc. Japan, 95, p. 825; Yoshio, M., Kazuo, M., Sumio, S., (1990) J. Ceram. Soc. Japan, 98, p. 1255; Berndt, C.C., Haddad, G.N., Farmer, A.J.D., Gross, K.A., (1990) Mater. Forum, 14 (3), p. 161; Koutsopoulos, S., (2002) J. Biomed. Mat. Res, 62, p. 600; Peña, J., Vallet-Regí, M., (2003) J. Europ. Ceram. Soc, 23, p. 1687; Orlovskii, V.P., Komlev, V.S., Barinov, S.M., (2002) Inorganic Materials, 38 (10), p. 973; Murry, M.G.S., wang, J., Pontom, C.B., Marquis, P.M., (1995) J. Mater. Sci, 30, p. 3061
Keywords: calcium phosphate; Calcium phosphates; Colloidal processing; Colloids; hydroxyapatite; Precipitated powders; precipitation; Precipitation (chemical); rheology; Stoichiometry; Surface active agents; Vacuum filtration; Washing

Method for tailoring and control the morphology, size and porosity of calcium phosphate granules - Lemos, A.F.; Rocha, J.H.G.; Ventura, J.M.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2005)
Hydroxyapatite (HA) is the calcium-phosphate material with composition closest to that of human bone, what makes it suitable for osseous implant purposes, namely as fillers, spacers and bone grafts substitutes. This study is aimed at the development of a method to produce porous spherical hydroxyapatite granules. The process involves the spraying of a suspension with different amounts of a setting agent to a setting media. The tailor and the control of the morphology, size and porosity of the granules were attained by adjusting the nozzle diameter, the pressure of air flow and the distance between the nozzle and the setting media.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Lemos, A.F.; Ceramic and Glass Engineering Department, Campus de Santiago, University of Aveiro, 3810-193 Aveiro, Portugal; email: ilemos@cv.ua.ptReferences: de Groot, K., (1983) Bioceramics of Calcium Phosphates, , CRC Press, Boca Raton, FL;Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, , World Scientific, London, UK; Elliot, J.C., (1994) Structure and chemistry of the apatites and other calcium orthophosphates. Studies in Organic Chemistry, 18. , Elsevier Science, Netherlands; Paul, W., Sharma, C.P., (1999) J. Mater. Sci.: Mater. Med, 10, p. 383; Ohgushi, H., Okumura, M., Yoshikawa, T., Inoue, K., Senpuku, N., Tamai, S., Shors, E.C., (1992) J. Biomed. Mater. Res, 26, p. 885; Liu, D., (1996) Biomaterials, 17, p. 1955; Komlev, V.S., Barinov, S.M., Koplik, E.V., (2002) Biomaterials, 23, p. 3449; Lamprecht, A., Shafer, U., Lehr, C., (2000) AAPS PharmSciTech, 3 (1), p. 17. , article; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., (2004) Materials Science Forum, 455-456, p. 361
Keywords: Air flow; Bioceramics; Bioceramlcs; Bone grafts substitutes; calcium phosphate; Granular materials; Granules; Human bone; hydroxyapatite; Hydroxyapatite granules; Porous materials; Porous structures; Starch

Mineralization of regenerated cellulose hydrogels induced by human bone marrow stromal cells - Granja, P.L.; De Jéso, B.; Bareille, R.; Rouais, F.; Baquey, C.; Barbosa, M.A. (European Cells and MaterialsEur. Cells and Mater., 2005)
The proliferation of cultured human bone marrow stromal cells (HBMSC) on regenerated cellulose hydrogels was assessed. Regenerated cellulose hydrogels showed good rates of HBMSC proliferation, the cells exhibiting a flattened morphology, and after 22 days in culture, the cells had homogeneously colonized the surface of the materials. Moreover, since the early days in culture, between the surface of the materials and attached cells a continuous granulated hydroxyapatite layer was formed. It has been previously demonstrated in vitro, but without cells, that these materials did not mineralize. Hence, it seems that HBMSC promoted the mineralization of the surface.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusPubMed ID: 16217723Language of Original Document: EnglishCorrespondence Address: Granja, P.L.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: pgranja@ineb.up.ptChemicals/CAS: cellulose, 61991-22-8, 68073-05-2, 9004-34-6; hydroxyapatite, 1306-06-5, 51198-94-8; Calcium Phosphates; Cellulose, 9004-34-6; Hydrogels; calcium phosphate, 10103-46-5References: (1994) Evaluation Biologique des Dispositifs Médicaux. Partie 5: Essais Concernant la Cytotoxicité: Méthodes in Vitro. (Biological Evaluation of Medical Devices. Part 5: Cytotoxicity Assays: in Vitro Methods), , www.afnor.fr, AFNOR-NF EN 30993-5. Association Française de Normalization, Saint-Denis la Plaine, France;Albrektsson, T., Hard tissue response (1998) Handbook Of Biomaterial Properties, pp. 500-512. , Black J, Hastings G (eds). Chapman & Hall, London; Amédée, J., Bareille, R., Jeandot, R., Bordenave, L., Remy, M., Rouais, F., Baquey, C., Evaluation of cell colonization on biomaterials: Preventing cell attachment to plastic containers (1994) Biomaterials, 15, pp. 1029-1031; Bergsma, J.E., De Bruijn, W.C., Rozema, F.R., Bos, R.R.M., Boering, G., Late degradation tissue response to poly(L-lactide) bone plates and screws (1995) Biomaterials, 16, pp. 25-31; Bohic, S., Heymann, D., Pouezat, J.A., Gauthier, O., Daculsi, G., Transmission FT-IR microspectroscopy of mineral phases in calcified tissues (1998) Sciences de la Vie, 321, pp. 865-876; Burgess, E.A., Hollinger, J.O., Options for engineering bone (1998) Frontiers in Tissue Engineering, pp. 383-399. , Patrick Jr CW, Mikos AG, McIntire LV (eds). Elsevier Science, Oxford; Chauveaux, D., Barbie, C., Barthe, X., Baquey, C., Poustis, J., Biological behaviour of cellulosic materials after bone implantation: Preliminary results (1990) Clin Mater, 5, pp. 251-258; Choee, J.H., Lee, S.J., Lee, Y.M., Rhee, J.M., Lee, H.B., Khang, G., Proliferation rate of fibroblast cells on polyethylene surfaces with wettability gradient (2004) J Appl Polym Sci, 92, pp. 599-606; Curtis, A.S.G., Forrester, J.V., Clark, P., Substrate hydroxylation and cell adhesion (1986) J Cell Sci, 86, pp. 9-24; Dasarathy, H., Riley, C., Coble, H.D., Analysis of apatite deposits on substrates (1993) J Biomed Mater Res, 27, pp. 477-482; Degenshein, G.A., Hurwitz, A., Ribacoff, S., Experience with regenerated oxidized cellulose (1963) NY State J Med, 63, pp. 2639-2643; Dias, G.J., Peplow, P.V., Teixeira, F., Osseous regeneration in the presence of oxidized cellulose and collagen (2003) J Mater Sci Mater Med, 14, pp. 739-745; Dumitriu, S., Dumitriu, M., Hydrogels as support for drug delivery systems (1996) Polysaccharides in Medicinal Applications, pp. 705-764. , Dumitriu S (ed.). Marcel Dekker, New York; Franz, G., Polysaccharides in pharmacy (1986) Adv Polym Sci, 76, pp. 1-30; Friedman, R.J., Black, J., Galante, J.O., Jacobs, J.J., Skinner, H.B., Current concepts in orthopaedic biomaterials and implant fixation (1993) J Bone Joint Surg, 75 A, pp. 1086-1109; Galgut, P.N., Oxidized cellulose mesh. I. Biodegradable membrane in periodontal surgery (1990) Biomaterials, 11, pp. 561-564; Granja, P.L., Pouységu, L., Deffieux, D., Daudé, G., De Jéso, B., Labrugère, C., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Surface chemical modification of regenerated cellulose hydrogels (2001) J Appl Polym Sci, 82, pp. 3354-3365; Granja, P.L., Pouységu, L., De Jéso, B., Rouais, F., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Mineralization of chemically modified regenerated cellulose hydrogels (2001) J Mater Sci, 36, pp. 2163-2172; Granja, P.L., Ribeiro, C.C., De Jéso, B., Baquey, C., Barbosa, M.A., Mineralization of regenerated cellulose hydrogels (2001) J Mater Sci: Mater Med, 12, pp. 785-791; Hayashi, T., Biodegradable polymers for biomedical uses (1994) Prog Polym Sci, 19, pp. 663-702; Healy, K.E., Thomas, C.H., Rezania, A., Kim, J.E., McKeown, P.J., Lom, B., Hockberger, P.E., Kinetics of bone cell organization and mineralization on materials with patterned surface chemistry (1996) Biomaterials, 17, pp. 195-208; Hon, D.N.-S., Cellulose and its derivatives: Structures, reactions, and medical uses (1996) Polysaccharides in Medicinal Applications, pp. 87-105. , Dumitriu D (ed.). Marcel Dekker, New York; Horbett, T.A., The role of adsorbed proteins in tissue response to biomaterials (2004) Biomaterials Science: An Introduction to Materials in Medicine, 2nd Ed., pp. 237-246. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (eds.). Elsevier-Academic Press, San Diego; Hosseini, M.M., Sodek, J., Franke, R.-P., Davies, J.E., The structure and composition of the bone-implant interface (2000) Bone Engineering, pp. 295-304. , Davies JE (ed.). em squared inc., Toronto; Ikada, Y., Biomedical applications of cellulose membranes (1989) Cellulose: Structural and Functional Aspects, pp. 447-455. , Kennedy JF, Phillips GO, Williams PA (eds.). Ellis Horwood, Chichester; Ishaug, S.L., Crane, G.M., Miller, M.J., Yasko, A.W., Yaszemski, M.J., Mikos, A.G., Bone formation by three-dimensional stromal osteoblast culture in biodegradable polymer scaffolds (1997) J Biomed Mater Res, 36, pp. 17-28; (1992) Biological Evaluation of Medical Devices. Test for Cytotoxicity: in Vitro Methods, , www.iso.org, ISO 10993-5. International Organization for Standardization, Geneva, Switzerland; Lamba, N.M.K., Baumgartner, J.A., Cooper, S.L., Cell-synthetic surface interactions (1998) Frontiers in Tissue Engineering, pp. 121-137. , Patrick Jr CW, Mikos AG, McIntire LV (eds). Elsevier Science, Oxford; Lee, J.H., Lee, J.W., Khang, G., Lee, H.B., Interaction of cells on chargeable functional group gradient surfaces (1997) Biomaterials, 18, pp. 351-358; Martson, M., Viljanto, J., Hurme, T., Saukko, P., Biocompatibility of cellulose sponge with bone (1998) Eur Surg Res, 30, pp. 426-432; Martson, M., Viljanto, J., Hurme, T., Laippala, P., Saukko, P., Is cellulose sponge degradable or stable as implantation materials? An in vivo subcutaneous study in the rat (1999) Biomaterials, 20, pp. 1899-1995; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., Attachment of cultured human bone cells to novel polymers (1999) J Biomed Mater Res, 44, pp. 1-11; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., Noishiki, Y., Tissue biocompatibility of cellulose and its derivatives (1989) J Biomed Mater Res, 23, pp. 125-133; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Meth, 65, pp. 55-63; Patrick Jr., C.W., Mikos, A.G., McIntire, L.V., Prospectus of tissue engineering (1998) Frontiers in Tissue Engineering, pp. 3-11. , Patrick Jr CW, Mikos AG, McIntire LV (eds). Elsevier Science, Oxford; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D., (1990), Biocompatible, hydrophilic material. Method of manufacture and uses of same (Fr Pat 8610331, 1986; Eur Pat 0256906 A1, 1987) US Pat 4904258Poustis, J., Baquey, C., Chauveaux, D., Mechanical properties of cellulose in orthopaedic devices and related environments (1994) Clin Mater, 16, pp. 119-124; Puleo, D.A., Bizios, R., Formation of focal contacts by osteoblasts cultured on orthopedic biomaterials (1992) J Biomed Mater Res, 26, pp. 291-301; Puleo, D.A., Nanci, A., Understanding and controlling the bone-implant interface (1999) Biomaterials, 20, pp. 2311-2321; Shelton, R.M., Rasmussen, A.C., Davies, J.E., Protein adsorption at the interface between charged polymer substrata and migrating osteoblasts (1988) Biomaterials, 9, pp. 24-29; Skoog, T., The use of periosteum and surgicel® for bone restoration in congenital clefts of the maxilla (1967) Scand J Plast Reconstr Surg, 1, pp. 113-130; Smetana Jr., K., Cell biology of hydrogels (1993) Biomaterials, 14, pp. 1046-1050; Uysal, A., Ozbek, S., Ozcan, M., Comparison of the biological activities of high-density porous polyethylene implants and oxidized regenerated cellulose-wrapped diced cartilage grafts (2003) Plast Reconstr Surg, 112, pp. 540-546; Vert, M., Mauduit, J., Li, S., Biodegradation of PLA/GA polymers: Increasing complexity (1994) Biomaterials, 15, pp. 1209-1213; Vilamitjana-Amédée, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., Human bone marrow stromal cells express an osteoblastic phenotype in culture (1993) In Vitro Cell Dev Biol, 29 A, pp. 699-707; Recum, H.A., Yaszemski, M.J., Mikos, A.G., Tissue engineering concepts (1999) Handbook of Biomaterials Evaluation: Scientific, Technical and Clinical Testing of Implant Materials, 2nd Ed., pp. 385-409. , von Recum AF (ed.), Edwards Brothers, Ann Arbor; Webb, K., Hlady, V., Tresco, P.A., Relative importance of surface wettability and charged functional groups on NIH 2T3 fibroblast attachment, spreading and cytoskeletal organization (1998) J Biomed Mater Res, 41, pp. 422-430; Yaszemski, M.J., Payne, R.G., Hayes, W.C., Langer, R., Mikos, A.G., Evolution of bone transplantation: Molecular, cellular and tissue strategies to engineer human bone (1996) Biomaterials, 17, pp. 175-185; Kristen, H., Bosch, P., Bednar, H., Plenk Jr., H., Biocompatibility of wood in bone tissue (1977) Arch Orthop Unfallchir, 89, pp. 1-14; Kristen, H., Bosch, P., Bednar, H., Plenk Jr., H., The effects of dynamic loading on intracalcaneal wood implants and on the tissues surrounding them (1979) Arch Orthop Trauma Surg, 93, pp. 287-292; Li, S.H., Liu, Q., De Wijn, J., Zhou, B.L., De Groot, K., Calcium phosphate formation induced on silica in bamboo (1997) J Mater Sci Mater Med, 8, pp. 427-433; Li, S.H., Liu, Q., De Wijn, J.R., Zhou, B.L., De Groot, K., In vitro calcium phosphate formation on a natural composite material, bamboo (1997) Biomaterials, 18, pp. 389-395
Keywords: article; bone marrow cell; Bone Marrow Cells; bone mineralization; Calcification, Physiologic; Calcium phosphates; Cell culture; cell proliferation; cell regeneration; Cells, Cultured; Cellulose; hematopoietic stem cell; human; Human bone marrow stromal cells; human cell; Humans; hydrogel; Hydrogels; hydroxyapatite; in vitro study; mineralization; Regenerated cellulose hydrogels; Regeneration; Spectroscopy, Fourier Transform Infrared; stroma cell; Stromal Cells; Time series analysis

Neural network classification: Maximizing zero-error density - Silva, L.M.; Alexandre, L.A.; De Sá, J.M. (Lecture Notes in Computer ScienceLect. Notes Comput. Sci., 2005)
We propose a new cost function for neural network classification: the error density at the origin. This method provides a simple objective function that can be easily plugged in the usual backpropagation algorithm, giving a simple and efficient learning scheme. Experimental work shows the effectiveness and superiority of the proposed method when compared to the usual mean square error criteria in four well known datasets. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 65875Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Silva, L.M.; Instituto de Engenharia Biomédica, Lab. de Sinai e Imagem Biomédica, Campus da FEUP, Rua Dr. Roberto Frias, 4200 - 465 Porto, PortugalReferences: Erdogmus, D., Principe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786;Erdogmus, D., Principe, J., Generalized information potential criterion for adaptive system training (2002) IEEE Transactions on Neural Networks, 13 (5), pp. 1035~1044; Santos, J.M., Alexandre, L.A., Marques De Sá, J., The error entropy minimization algorithm for neural network classification (2004) Int. Conf. on Recent Advances in Soft Computing, , Nottingham, United Kingdom; Santos, J.M., Alexandre, L.A., De Sa, J.M., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, and O. Ersoy, editors, ASME Press Series; Silva, L.M., De Sa, J.M., Alexandre, L.A., Neural network classification using shannon's entropy (2005) European Symposium on Artificial Neural Networks; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Blake, C.L., Merz, C.J., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html, University of California, Irvine, Dept. of Information and Computer Sciences
Keywords: Algorithms; Backpropagation; Backpropagation algorithm; Classification (of information); Costs; Error analysis; Function evaluation; Learning systems; Mean square error; Neural network classification; Neural networks; Zero-error density

Neural networks trained with the EEM algorithm: Tuning the smoothing parameter - Santos, J.M.; Marques de Sá, J.; Alexandre, L.A. (WSEAS Transactions on SystemsWSEAS Trans. Syst., 2005)
The training of Neural Networks and particularly Multi-Layer Perceptrons (MLP's) is made by minimizing an error function usually known as "cost function". In our previous works, we apply the Error Entropy Minimization (EEM) algorithm in classification and its optimized version using, as cost function, the entropy of the errors between the outputs and the desired targets of the neural network. One of the difficulties in implementing the EEM algorithm is the choice of the smoothing parameter, also known as window size, in the Parzen Window probability density function estimation for the computation of the entropy and its gradient. We present here a formula yielding the value of the smoothing parameter, depending on the number of data samples and on the neural network output dimension. Several experiments with real data sets were made in order to show the validity of the proposed formula.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Santos, J.M.; Intituto de Engenharia Biomédica, Porto, Portugal; email: jms@isep.ipp.ptReferences: Erdogmus, D., Principe, J., "An Error-Entropy Minimization Algorithm for Supervised Training of Nonlinear Adaptive Systems" (2002) Trans. On Signal Processing, 50 (7), pp. 1780-1786;Santos, J.M., Alexandre, L.A., Marques de Sá, J., "The error entropy minimization algorithm for neural network classification" (2004) Proceedings of the 5th International Conference on Recent Advances in Soft Computing, pp. 92-97. , A. Lofti, Ed. Nottingham Trent University; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Sereno, F., "Optimization of the error entropy minimization algorithm for neural network classification" (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C.H. Dagli, A.L. Buczak, D.L. Enke, M.J. Embrechts, and O. Ersoy, Eds., ASME Press; Erdogmus, D., Principe, J., "Entropy Minimization Algorithm for Neural Networks" (2001) Proceedings of the Intl. Joint Conf. on Neural Networks, pp. 3003-3008; Xu, D., Princpe, J., "Training mlps layer-by-layer with the information potential" (1999) Intl. Joint Conf. on Neural Networks, pp. 1716-1720; Silverman, B.W., (1986) Density Estimation for Statistics and Data Analisys, 26. , Chapman & Hall; Bowman, A.W., Azzalini, A., (1997) Applied Smooting Techniques for Data Analysis, , London: Oxford University Press; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., "Adaptive mixtures of local experts" (1991) Neural Computation, pp. 79-87
Keywords: Cost function; entropy; Error entropy minimization (EEM) algorithm; Learning algorithms; Learning systems; Neural networks; Optimization; Parzen; Probability density function; Smoothing parameter

Polysaccharides as scaffolds for bone regeneration - Barbosa, M.A.; Granja, P.L.; Barrias, C.C.; Amaral, I.F. (ITBM-RBMITBM-RBM, 2005)
This review is concerned with the use of polysaccharides for bone regeneration. Cellulose, alginate and chitosan have been chosen as examples of the formidable potential of this class of materials. Many others could be cited but our experience and research interests dictated the choice. As in many areas of research we know how they started but we cannot see how and if they will end. Modification of cellulose was our entrance to the world of polysaccharides and a lot of what we know we owe to Charles Baquey, to whom we would like to express our immense gratitude. This chapter is dedicated to him, for his cooperation, unlimited enthusiasm and friendship. © 2005 Elsevier SAS. All rights reserved.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: ITBMFdoi: 10.1016/j.rbmret.2005.04.006Language of Original Document: EnglishCorrespondence Address: Barbosa, M.A.; INEB, Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: mbarbosa@ibmc.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; arginylglycylaspartic acid, 99896-85-2; cellulose, 61991-22-8, 68073-05-2, 9004-34-6; chitosan, 9012-76-4References: Shogren, R.L., Bagley, E.B., Natural polymers as advanced materials: Some research needs and directions (1999) Biopolymers. Utilizing Nature's Advanced Materials, ACS Symposium Series 723, pp. 2-11. , S.H. Iman R.V. Greene B.R. Zaidi Oxford University Press Cary, USA;Kaplan, D.L., Introduction to polymers from renewable resources (1998) Biopolymers from Renewable Resources, pp. 1-29. , D.L. Kaplan Springer Verlag Berlin, Germany; Yannas, I.V., Natural materials (1996) Biomaterials Science. An Introduction to Materials in Medicine, pp. 84-94. , B.D. Ratner A.S. Hoffman F.J. Schoen J.E. Lemons Academic Press California, USA; Hon, D.-S., Cellulose and its derivatives: Structures, reactions, and medical uses (1996) Polysaccharides in Medicinal Applications, pp. 87-105. , S. Dumitriu Marcel Dekker New York, USA; Okajima, K., Role of molecular characteristics on some physiological properties of cellulose derivatives (1989) Cellulose: Structural and Functional Aspects, pp. 439-446. , J.F. Kennedy G.O. Phillips P.A. Williams Ellis Horwood Chichester, UK; Ikada, Y., Biomedical applications of cellulose membranes Cellulose: Structural and Functional Aspects, pp. 447-455; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., Noishiki, Y., Tissue biocompatibility of cellulose and its derivatives (1989) J. Biomed. Mater. Res., 23, pp. 125-133; Hayashi, T., Biodegradable polymers for biomedical uses (1994) Prog. Polym. Sci., 19, pp. 663-702; Klemm, D., Philipp, B., Heinze, T., Heinze, U., Wagenknecht, W., (1998) Comprehensive Cellulose Chemistry, Vol 1, Fundamentals and Analytical Methods and Functionalization of Cellulose, Vol. 2, , Wiley-VCH Weinheim, Germany; Hon, D.-S., Cellulose and its derivatives: Structures, reactions, and medical uses (1996) Polysaccharides in Medicinal Applications, pp. 87-105. , S. Dumitriu Marcel Dekker New York, USA; Nevell, T.P., Zeronian, S.H., (1985) Cellulose Chemistry and Its Applications, , Ellis Horwood Chichester, UK; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D., Biocompatible, hydrophilic material. Method of manufacture and uses of same. Fr Pat 8610331, 1986; Eur Pat 0256906 A1, 1987; US Pat 4904258, 1990Baquey, C., Chauveuax, D., Poustis, J., La cellulose: Un vieux mat́riau pour le developpement de biomat́riaux innovants (1992) Sci. Tech. Technol., 20, pp. 28-32; Barbí, C., Chauveaux, D., Baquey, C., Poustis, J., Pommier, J.C., Morlier, R., Évaluation des propriet́s mecaniques de mat́riaux cellulosiques et perspectives d'application originales de ces mat́riaux en chirurgie orthoṕdique (1987) Calcified Tissues and Biomaterials, pp. 319-325. , Proc BIOMAT 87 Congress Bordeaux, France; Barbí, C., Bareille, R., Harmand, M.-F., Baquey, C., Cellulosic materials for skeletal reparation: Mechanical, physical and biological in vitro behaviour (1989) Calcified Tissues and Biomaterials, , Proc BIOMAT 89 Congress Bordeaux, France; Brie, J., Lafage, M.H., Chauveaux, D., Gueroult, J.M., Poustis, J., Baquey, C., La cellulose macroporeuse: Un mat́riau potentiellement utilisable pour le comblement osseux (1992) Biomat́riaux et Organes Artificiels, , Proc BIOMAT 92 Congress Bordeaux, France; Poustis, J., Chauveaux, D., Baquey, C., (1992) Dynamic Testing of Cellulose in Orthopaedics Devices and Related Environments, p. 191. , 4th World Biomaterials Congr Berlin, Germany; Poustis, J., Baquey, C., Chauveaux, D., Mechanical properties of cellulose in orthopaedic devices and related environments (1994) Clin. Mater., 16, pp. 119-124; Chauveaux, D., Gueroult, J.-M., Barbí, C., Baquey, C., Cellulosic materials for skeletal reparation: Preliminary study of in vivo biocompatibility (1989) Calcified Tissues and Biomaterials, , Proc BIOMAT 89 Congress Bordeaux, France; Barbie, C., Chauveaux, D., Barthe, X., Baquey, C., Poustis, J., Biological behaviour of cellulosic materials after bone implantation: Preliminary results (1990) Clin. Mater., 5, pp. 251-258; Gross, U., Muller-Mai, C., Voigt, C., (1992) The Tissue Response on Cellulose Cylinders after Implantation in the Distal Femur of Rabbits, p. 192. , 4th World Biomaterials Congr Berlin, Germany; Baquey, C., Barbí, C., More, N., Rouais, F., Poustis, J., Chauveaux, D., (1992) In Vivo Study of the Biostability of a Cellulose Material, p. 365. , 4th World Biomaterials Congr Berlin, Germany; Mizusawa, Y., Burke, J.R., Prednisolone and cellulose phosphate treatment in idiopathic infantile hypercalcaemia with nephrocalcinosis (1996) J. Pediatr. Child Health, 32, pp. 350-352; Parfitt, A.M., Effect of cellulose phosphate on calcium and magnesium homeostasis: Studies in normal subjects and patients with latent hypoparathyroidism (1975) Clin. Sci. Mol. Med., 49, pp. 83-90; Pak, C.Y.C., Delea, C.S., Bartter, F.C., Successful treatment of recurrent nephrolithiasis (calcium stones) with cellulose phosphate (1974) N. Engl. J. Med., 290, pp. 175-180; Dowd, V., Yon, R.J., Heterogeneous binding of aldolase to phosphocellulose. Interpretation in terms of a "concerted cluster" model of multivalent affinity (1992) J. Chromatogr., 627, pp. 145-151; Sugihara, J., Imamura, T., Yanase, T., Separation of peptides by cellulose-phosphate chromatography for identification of a hemoglobin variant (1982) J. Chromatogr., 229, pp. 193-199; Granja, P.L., Pouyśgu, L., Ṕtraud, M., De J́so, B., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Synthesis and characterization of highly phosphorylated cellulose gels (2001) J. Appl. Polym. Sci., 82, pp. 3341-3353; Granja, P.L., Pouyśgu, L., Deffieux, D., Daud́, G., De J́so, B., Labrug̀re, C., Cellulose phosphates as biomaterials. Surface chemical modification of regenerated cellulose hydrogels (2001) J. Appl. Polym. Sci., 82, pp. 3354-3365; Granja, P.L., Pouyśgu, L., De J́so, B., Rouais, F., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Mineralization of chemically modified regenerated cellulose hydrogels (2001) J. Mater. Sci., 36, pp. 2163-2172; Granja, P.L., Ribeiro, C.C., De J́so, B., Baquey, C., Barbosa, M.A., Mineralization of regenerated cellulose hydrogels (2001) J. Mater. Sci. Mater. Med., 12, pp. 785-791; Granja, P.L., De J́so, B., Bareille, R., Rouais, F., Baquey, C., Barbosa, M.A., (2004) Cellulose Phosphates As Biomaterials. in Vitro Biocompatibility Studies; Granja, P.L., De J́so, B., Bareille, R., Rouais, F., Baquey, C., Barbosa, M.A., (2004) Mineralization of Regenerated Cellulose Hydrogels Induced by Human Osteoprogenitor Cells; Fricain, J.C., Granja, P.L., Barbosa, M.A., De J́so, B., Barthe, N., Baquey, C., Cellulose phosphates as biomaterials. in vivo biocompatibility studies (2001) Biomaterials, 23, pp. 971-980; Franz, G., Polysaccharides in pharmacy (1986) Adv. Polym. Sci., 76, pp. 1-30; Skoog, T., The use of periosteum and surgicel® for bone restoration in congenital clefts of the maxilla (1967) Scand. J. Plast. Reconstr. Surg., 1, pp. 113-130; Degenshein, G.A., Hurwitz, A., Ribacoff, S., Experience with regenerated oxidized cellulose (1963) N. Y. State J. Med., 63, pp. 2639-2643; Finn, M.D., Schow, S.R., Schneiderman, E.D., Osseous regeneration in the presence of four common hemostatic agents (1992) J. Oral Maxillofac. Surg., 50, pp. 608-612; Galgut, P.N., Oxidized cellulose mesh. I. Biodegradable membrane in periodontal surgery (1990) Biomaterials, 11, pp. 561-564; Matthew, I.R., Browne, R.M., Frame, J.W., Millar, B.G., Subperiosteal behaviour of alginate and cellulose wound dressing materials (1995) Biomaterials, 16, pp. 275-278; Galgut, P.N., Oxidized cellulose mesh. II. Using hydroxy-apatite bone grafting material in the treatment of intrabony deffects (1990) Biomaterials, 11, pp. 565-567; De Taillac, L.B., Fricain, J.C., Barthe, N., Brouillaud, B., Labrugere, C., Bareille, R., Validation du concept de materiaux hybrids a base de cellulose macroporeuse - Application a l'odontologie (2004) Les Cahiers de l'Adf, 1617, pp. 18-25; De Taillac, L.B., (2004), Ph.D. Thesis. University of Bordeaux 1. DecemberMartson, M., Viljanto, J., Hurme, T., Saukko, P., Biocompatibility of cellulose sponge with bone (1998) Eur. Surg. Res., 30, pp. 426-432; Martson, M., Viljanto, J., Hurme, T., Laippala, P., Saukko, P., Is cellulose sponge degradable or stable as implantation materials? An in vivo subcutaneous study in the rat (1999) Biomaterials, 20, pp. 1899-1995; Pajulo, O., Viljanto, J., Lonnberg, B., Hurme, T., Lonnqvist, K., Saukko, P., Viscose cellulose sponge as an implantable matrix: Changes in the structure increase the production of granulation tissue (1996) J. Biomed. Mater. Res., 32, pp. 439-446; De Taillac, L.B., Porte, M.C., Bareille, R., Amedee, J., Labrugere, C., Fortin, F., (2002) Development of a New Generation of Bone Substitute - Covalenet Immobilization of the Active Peptides onto Cellulose, , Society for Biomaterials Conference Florida, USA; De Taillac, L.B., Labrugere, C., Amedee, J., Bareille, R., Fricain, J.C., Fortin, F., (2002) Human Osteoblasts Interaction with Adhesion Peptides Grafted onto Cellulose, , 17th European Conference on Biomaterials Barcelona, Spain; De Taillac, L.B., Porte-Durrieu, M.C., Labrugere, C., Bareille, R., Aḿd́e, J., Baquey, C., Grafting of RGD peptides to cellulose to enhance human osteoprogenitor cells adhesion and proliferation (2004) Compos. Sci. Technol., 64, pp. 775-915; Gombotz, W.R., Wee, S.F., Protein release from alginate matrices (1998) Adv. Drug Deliv. Rev., 31, pp. 267-285; Smidsrod, O., Draget, K.I., Chemistry and physical properties of alginates (1996) Carbohydr. Eur., 14, pp. 6-13; Eiselt, P., Yeh, J., Latvala, R.K., Shea, L.D., Mooney, D.J., Porous carriers for biomedical applications based on alginate hydrogels (2000) Biomaterials, 21, pp. 1921-1927; Alsberg, V., Anderson, K., Albeiruti, A., Franceshi, R.T., Mooney, D.J., Cell interactive alginate hydrogels for bone tissue engineering (2001) J. Dent. Res., 80, pp. 2025-2029; Barrias, C.C., Granja, P.L., Meriem, L., Sá Miranda, M.C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localised delivery of a therapeutic enzyme (2005) J. Biomed. Mater Res.; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Dalby, M.J., Di Silvio, L., Harper, E.J., Bonfield, W., Increasing hydroxyapatite incorporation into poly(methylmethacrylate) cement increases osteoblast adhesion and response (2002) Biomaterials, 23, pp. 569-576; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373; Barrias, C.C., Ribeiro, C.C., Sá Miranda, M.C., Barbosa, M.A., Effect of calcium phosphate addition to alginate microspheres: Modulation of enzyme release kinetics and improvement of osteoblastic cell adhesion (2005) Key Eng. Mater., 284-286, pp. 689-692; Khor, E., (2001) Chitin: Fulfilling a Biomaterials Promise. 1st Ed, , Elsevier Oxford, UK; Vandevord, P.J., Matthew, H.W.T., Desilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J. Biomed. Mater. Res., 59, pp. 585-590; Roberts, G.A.F., (1992) Chitin Chemistry, , The Macmillan Press Houndmills; Domard, A., Chitosan interactions Advances in Chitin Science, pp. 410-420. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher (1007); Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18, pp. 567-575; Muzzarelli, R.A.A., Human enzymatic activities related to the therapeutic administration of chitin derivatives (1997) Cell. Mol. Life Sci., 53, pp. 131-140; Muzzarelli, R.A.A., Muzzarelli, C., Natural and artificial chitosan-inorganic composites, a mini-review (2002) Chitosan in Pharmacy and Chemistry: Atec Edizioni, pp. 233-244. , R.A.A. Muzzarelli C. Muzzarelli; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J. Control. Release, 78, pp. 187-197; Madihally, S.V., Matthew, H.W.T., Porous chitosan scaffolds for tissue engineering (1999) Biomaterials, 20, pp. 1133-1142; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Eng., 8, pp. 1009-1016; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., Chitosan supports the expression of extracellular matrix proteins in human osteoblasts and chondrocytes (2000) J. Biomed. Mater. Res., 51, pp. 586-595; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Preparation and histological evaluation of biomimetic three-dimensional hydroxyapatite/chitosan-gelatin network composite scaffolds (2002) Biomaterials, 23, pp. 3227-3234; Chatelet, C., Damour, O., Domard, A., Influence of the degree of acetylation on some biological properties of chitosan films (2001) Biomaterials, 22, pp. 261-268; Dhiman, H.K., Ray, A.R., Panda, A.K., Characterization and evaluation of chitosan matrix for in vitro growth of MCF-7 breast cancer cell lines (2004) Biomaterials, 25, pp. 5147-5154; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., Cellular responses to chitosan in vitro: The importance of deacetylation (2000) J. Mater. Sci. Mater. Med., 11, pp. 773-778; Amaral, I.F., Granja, P.L., Barbosa, M.A., In vitro mineralisation of chitosan membranes carrying phosphate functionalities (2004) Key Eng. Mater., 254-256, pp. 577-580
Keywords: Alginate; alginic acid; Amino Acid Sequence; arginylglycylaspartic acid; biomaterial; biotechnology; bone cell; bone prosthesis; Bone Regeneration; Cellulose; chitosan; enzyme degradation; polysaccharide; Polysaccharides; review; Tissue engineering

Porous HA scaffolds for drug releasing - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2005)
Dense and porous hydroxyapatite materials aimed at being used in controlled drug delivery, were characterised and studied in order to evaluate their ability to adsorb and release sodium ampicillin in a controlled manner, as a model for a drug delivery system, potentially applicable associated to surgery for the treatment of bone defects. These porous materials should also have adequate mechanical strength to withstand manipulation and sculpturing in surgery room. Adsorption and release profiles were obtained for a range of porous materials, leading to higher adsorption rates and more adequate release profiles than for dense materials.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB, Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: aqueiroz@ineb.up.ptReferences: Queiroz, A.C., (2001) Biomaterials, 22, p. 1393
Keywords: Adsorption; ampicillin; Controlled drug delivery; Drug release; hydroxyapatite; orthopedics; Porous hydroxyapatite; Porous hydroxyapatites; Porous materials; Scaffolds; Sodium ampicillin; Surgery; Surgery rooms

Proliferation, activity, and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres - Barrias, C.C.; Ribeiro, C.C.; Lamghari, M.; Sá Miranda, C.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
In this study, the behavior of bone marrow stromal cells cultured on calcium titanium phosphate (CTP) microspheres was analyzed. Cell adhesion and proliferation were estimated by the neutral red assay and by total DNA quantification. Morphology and deposition of extracellular matrix were assessed by confocal laser scanning microscopy and/or scanning electron microscopy. The expression of the osteoblastic phenotype was evaluated by monitoring alkaline phosphatase activity and osteocalcin secretion. Results revealed that cells were able to attach and spread on the surface of CTP microspheres, and gradually grow into nearly confluent monolayers. Moreover, cells were able to bridge adjacent microspheres forming microsphere-cell clusters. Cells produced an abundant amount of fibrillar extracellular matrix that covered the substrate surface. Alkaline phosphatase activity peaked around days 7-14 and then decreased until day 21. Cells secreted osteocalcin, with higher levels being detected at day 14 than at day 21. Taken together, these results suggest that CTP microspheres are appropriate scaffolds for the growth and differentiation of cells along the osteoblastic lineage. © 2004 Wiley Periodicals, Inc.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30217PubMed ID: 15543603Language of Original Document: EnglishCorrespondence Address: Barrias, C.C.; INEB, Instituto de Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; osteocalcin, 136461-80-8; titanium, 7440-32-6; Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Osteocalcin, 104982-03-8; titanium phosphate, 17017-57-1; Titanium, 7440-32-6References: Senuma, Y., Franceschin, S., Hilborn, J.G., Tissieres, P., Bisson, I., Frey, P., Bioresorbable microspheres by spinning disk atomization as injectable cell carrier: From preparation to in vitro evaluation (2000) Biomaterials, 21 (11), pp. 1135-1144;Hsu, F.Y., Chueh, S.C., Wang, Y.J., Microspheres of hydroxyapatite/ reconstituted collagen as supports for osteoblast cell growth (1999) Biomaterials, 20 (20), pp. 1931-1936; McGlohorn, J.B., Grimes, L.W., Webster, S.S., Burg, K.J., Characterization of cellular carriers for use in injectable tissue-engineering composites (2003) J Biomed Mater Res, 66 A (3), pp. 441-449; Wu, T.J., Huang, H.H., Lan, C.W., Lin, C.H., Hsu, F.Y., Wang, Y.J., Studies on the microspheres comprised of reconstituted collagen and hydroxyapatite (2004) Biomaterials, 25 (4), pp. 651-658; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Key Eng Mater, 254-256, pp. 877-880; Van Wezel, A.L., Microcarrier technology: Present status and prospects (1983) Dev Biol Stand, 55, pp. 3-9; Malda, J., Kreijveld, E., Temenoff, J.S., Van Blitterswijk, C.A., Riesle, J., Expansion of human nasal chondrocytes on macroporous microcarriers enhances redifferendation (2003) Biomaterials, 24 (28), pp. 5153-5161; Frondoza, C., Sohrabi, A., Hungerford, D., Human chondrocytes proliferate and produce matrix components in microcarrier suspension culture (1996) Biomaterials, 17 (9), pp. 879-888; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., A novel route for the preparation of injectable ceramic porous microspheres for bone tissue engineering (2003) Ceramics, Cells and Tissues Annual Conferences: Bioceramic Surfaces Behavior in Vitro and in Vivo, pp. 228-232. , Ravaglioli A, Krajewski A, editors. Faenza: ISTEC-CNR editions; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., (2004) Preparation and Characterisation of Calcium-phosphate Microspheres for Biomedical Applications, , Submitted for publication; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254 (2), pp. 317-330; Labarca, C., Paigen, K., Simple, rapid, and sensitive DNA assay procedure (1980) Anal Biochem, 102 (2), pp. 344-352; Mankani, M.H., Kuznetsov, S.A., Fowler, B., Kingman, A., Robey, P.G., In vivo bone formation by human bone marrow stromal cells: Effect of carrier particle size and shape (2001) Biotechnol Bioeng, 72 (1), pp. 96-107; Higashi, T., Okamoto, H., Influence of particle size of calcium phosphate ceramics as a capping agent on the formation of a hard tissue barrier in amputated dental pulp (1996) J Endod, 22 (6), pp. 281-283; Misiek, D.J., Kent, J.N., Carr, R.F., Soft tissue responses to hydroxylapatite particles of different shapes (1984) J Oral Maxillofac Surg, 42 (3), pp. 150-160; Maniatopoulos, C., Bone formation by young adult bone marrow stromal cells in vitro (1987) J Dent Res, 66, p. 104; Pittenger, M.F., Mackay, A.M., Beck, S.C., Jaiswal, R.K., Douglas, R., Mosca, J.D., Moorman, M.A., Marshak, D.R., Multilineage potential of adult human mesenchymal stem cells (1999) Science, 284 (5411), pp. 143-147; Ter Brugge, P.J., Jansen, J.A., In vitro osteogenic differentiation of rat bone marrow cells subcultured with and without dexamethasone (2002) Tissue Eng, 8 (2), pp. 321-331; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21 (7), pp. 667-681; Anselme, K., Linez, P., Bigerelle, M., Le Maguer, D., Le Maguer, A., Hardouin, P., Hildebrand, H.F., Leroy, J.M., The relative influence of the topography and chemistry of TiA16V4 surfaces on osteoblastic cell behaviour (2000) Biomaterials, 21 (15), pp. 1567-1577; Deligianni, D.D., Katsala, N.D., Koutsoukos, P.G., Missirlis, Y.F., Effect of surface roughness of hydroxyapatite on human bone marrow cell adhesion, proliferation, differentiation and detachment strength (2001) Biomaterials, 22 (1), pp. 87-96; Boyan, B.D., Lossdorfer, S., Wang, L., Zhao, G., Lohmann, C.H., Cochran, D.L., Schwartz, Z., Osteoblasts generate an osteogenic microenvironment when grown on surfaces with rough microtopographies (2003) Eur Cell Mater, 6, pp. 22-27; Brunette, D.M., The effects of implant surface topography on the behavior of cells (1988) Int J Oral Maxillofac Implants, 3 (4), pp. 231-246; Schwartz, Z., Lohmann, C.H., Oefinger, J., Bonewald, L.F., Dean, D.D., Boyan, B.D., Implant surface characteristics modulate differentiation behavior of cells in the osteoblastic lineage (1999) Adv Dent Res, 13, pp. 38-48; Shu, R., McMullen, R., Baumann, M.J., McCabe, L.R., Hydroxyapatite accelerates differentiation and suppresses growth of MC3T3-E1 osteoblasts (2003) J Biomed Mater Res, 67 A (4), pp. 1196-1204; Nordstrom, E., Ohgushi, H., Yoshikawa, T., Yokobori, A.T., Yokobori, T., Osteogenic differentiation of cultured marrow stromal stem cells on surface of microporous hydroxyapatite based mica composite and macroporous synthetic hydroxyapatite (1999) Biomed Mater Eng, 9 (1), pp. 21-26; Oreffo, R.O.C., Driessens, F.C.M., Flanell, J.A., Triffitt, J.T., Growth and differentiation of human bone marrow osteoprogenitors on novel calcium phosphate cements (1998) Biomaterials, 19 (20), pp. 1845-1854; Knabe, C., Berger, G., Gildenhaar, R., Klar, F., Zreiqat, H., The modulation of osteogenesis in vitro by calcium titanium phosphate coatings (2004) Biomaterials, 25, pp. 4911-4919
Keywords: alkaline phosphatase; animal cell; Animals; article; Bioassay; Bone; bone marrow cell; Bone Marrow Cells; bone marrow stromal cell; Bone marrow stromal cells; Calcium; Calcium Compounds; calcium phosphate; Calcium titanium phosphate; cell adhesion; Cell culture; cell differentiation; cell growth; cell lineage; cell proliferation; cell structure; Confluent monolayers; confocal laser microscopy; Confocal laser scanning microscopy; controlled study; Deposition; DNA determination; enzyme activity; Enzyme kinetics; extracellular matrix; Microscopy, Electron; microsphere; Microspheres; nonhuman; osteoblast; osteocalcin; Osteogenesis; Osteogenic differentiation; phenotype; protein expression; protein secretion; rat; Rats; Scanning electron microscopy; Stromal Cells; surface property; Tissue culture; Tissue engineering; Titanium; unclassified drug

Rat bone marrow stromal cell osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation - Amaral, I.F.; Lamghari, M.; Sousa, S.R.; Sampaio, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Cell adhesion, migration, and proliferation of a few anchorage-dependent cells cultured on chitosan (Ch) matrices are influenced by the degree of N-acetylation (DA) of Ch. In the present work, we examined the influence of the DA on the attachment, spreading, proliferation, and osteogenic differentiation of rat bone marrow stromal cells (rBM-SCs). Ch membranes were characterized in terms of surface morphology, roughness, and wettability, and in terms of adsorption of an adhesive protein, fibronectin (Fn). Chs with DAs in the range of 4 to 49% were used. Among the Ch samples, the DA of 4% led to the highest Fn surface concentration, both from single protein solution and from diluted serum. Furthermore, the levels of Fn adsorbed from serum found for this DA were threefold higher than for the tissue culture polystyrene control, indicating that in the presence of competitive proteins Ch is more specific toward Fn adsorption than tissue culture polystyrene. rBMSCs cultured on Ch carrying a DA of 4% were able to spread, proliferate, and differentiate, reaching a higher level of osteogenic differentiation than on the control, despite the lower cell attachment observed for all Ch samples. Because the Ch sample with a DA of 4% showed the highest Fn adsorption from serum, we suggest that cell adhesion, spreading, and osteogenic differentiation of rBMSCs on Ch may be mediated by the adsorbed layer of Fn. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30436PubMed ID: 16092111Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; fibronectin, 86088-83-7; polystyrene, 9003-53-6; Chitosan, 9012-76-4; Coated Materials, Biocompatible; FibronectinsReferences: VandeVord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59 (3), pp. 585-590;Muzzarelli, R.A.A., Human enzymatic activities related to the therapeutic administration of chitin derivatives (1997) Cell Mol Life Sci, (53), pp. 131-140; Peluso, G., Petillo, O., Ranieri, M., Santin, M., Ambrosio, L., Calabro, D., Avallone, B., Balsamo, G., Chitosan-mediated stimulation of macrophage function (1994) Biomaterials, 15 (15), pp. 1215-1220; Muzzarelli, R.A.A., Mattiolibelmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., Stimulatory effect on bone-formation exerted by a modified chitosan (1994) Biomaterials, 15 (13), pp. 1075-1081; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Controlled Release, 78 (1-3), pp. 187-197; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., Vascular cell responses to polysaccharide materials: In vitro and in vivo evaluations (2000) Biomaterials, 21 (22), pp. 2315-2322; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., Chitosan supports the expression of extracellular matrix proteins in human osteoblasts and chondrocytes (2000) J Biomed Mater Res, 51 (4), pp. 586-595; Klokkevold, P.R., Vandemark, L., Kenney, E.B., Bernard, G.W., Osteogenesis enhanced by chitosan (poly-N-acetyl glucosaminoglycan) in vitro (1996) J Periodontol, 67 (11), pp. 1170-1175; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18 (7), pp. 567-575; Chatelet, C., Damour, O., Domard, A., Influence of the degree of acetylation on some biological properties of chitosan films (2001) Biomaterials, 22 (3), pp. 261-268; Dhiman, H.K., Ray, A.R., Panda, A.K., Characterization and evaluation of chitosan matrix for in vitro growth of MCF-7 breast cancer cell lines (2004) Biomaterials, 25 (21), pp. 5147-5154; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., Cellular responses to chitosan in vitro: The importance of deacetylation (2000) J Mater Sci Mater Med, 11 (12), pp. 773-778; Rainaldi, G., Filippini, P., Ferrante, A., Indovina, P.L., Santini, M.T., Fibronectin facilitates adhesion of K562 leukemic cells normally growing in suspension to cationic surfaces (2001) J Biomed Mater Res, 55 (1), pp. 104-113; Faucheux, N., Schweiss, R., Lutzow, K., Werner, C., Groth, T., Self-assembled monolayers with different terminating groups as model substrates for cell adhesion studies (2004) Biomaterials, 25 (14), pp. 2721-2730; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: Consequences for valve endothelial cell growth on tissue-engineering materials (2003) J Biomed Mater Res, 67 A (2), pp. 538-547; Bumgardner, J.D., Wiser, R., Elder, S.H., Jouett, R., Yang, Y., Ong, J.L., Contact angle, protein adsorption and osteoblast precursor cell attachment to chitosan coatings bonded to titanium (2003) J Biomater Sci Polym Ed, 14 (12), pp. 1401-1409; Gong, H.P., Zhong, Y.H., Li, J.C., Gong, Y.D., Zhao, N.M., Zhang, X.F., Studies on nerve cell affinity of chitosan-derived materials (2000) J Biomed Mater Res, 52 (2), pp. 285-295; Benesch, J., Tengvall, P., Blood protein adsorption onto chitosan (2002) Biomaterials, 23 (12), pp. 2561-2568; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42 (8), pp. 3569-3580; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., Highly deacetylated chitosan and its properties (1983) J Appl Polym Sci, 28 (6), pp. 1909-1917; Aiba, S., Studies on chitosan: 1. Determination of the degree of N-acetylation of chitosan by ultraviolet spectrophotometry and gel-permeation chromatography (1986) Int J Biol Macromol, 8 (3), pp. 173-176; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., Improved method for i.r. determination of the degree of N-acetylation of chitosan (1992) Int J Biol Macromol, 14 (3), pp. 166-169; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29 (1), pp. 63-68; Grundke, K., Bogumil, T., Werner, C., Janke, A., Poschel, K., Jacobasch, H.J., Liquid-fluid contact angle measurements on hydrophilic cellulosic materials (1996) Colloids Surf A, 116 (1-2), pp. 79-91; Slack, M., Properties of biological fluids (2004) Biomaterials Science: An Introduction to Materials in Medicine, pp. 813-817. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE, editors. Amsterdam: Elsevier; Du, Y.J., Cornelius, R.M., Brash, J.L., Measurement of protein adsorption to gold surface by radioiodination methods: Suppression of free iodide Sorption (2000) Colloids Surf B, 17 (1), pp. 59-67; (1993) Iodine-125, a Guide to Radioiodination Techniques, p. 64. , Little Chalfont, Buckinghamshire, UK: Amersham International; Sousa, S.R., Moradas-Ferreira, P., Saramago, B., Melo, L.V., Barbosa, M.A., Human serum albumin adsorption on TiO2 from single protein solutions and from plasma (2004) Langmuir, 20 (22), pp. 9745-9754; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone-formation in vitro by stromal cells obtained from bone-marrow of young-adult rats (1988) Cell Tissue Res, 254 (2), pp. 317-330; Ashton, B.A., Abdullah, F., Cave, J., Williamson, M., Sykes, B.C., Couch, M., Poser, J.W., Characterization of cells with high alkaline-phosphatase activity derived from human-bone and marrow: Preliminary assessment of their osteogenicity (1985) Bone, 6 (5), pp. 313-319; Huang, R.Y.M., Moon, G.Y., Pal, R., Chitosan/anionic surfactant complex membranes for the pervaporation separation of methanol/MTBE and characterization of the polymer/surfactant system (2001) J Membr Sei, 184 (1), pp. 1-15; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., Substrate dependent differences in morphology and elasticity of living osteoblasts investigated by atomic force microscopy (2000) Colloids Surf B, 19 (4), pp. 367-379; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21 (7), pp. 667-681; Domard, A., Chitosan interactions (1997) Advances in Chitin Science, pp. 410-420. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher; Smidsrod, O., Ottoy, M.H., Anthonsen, M.W., Varum, K.M., Solution properties of chitosan (1997) Advances in Chitin Science, pp. 402-409. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher; Fee, M., Errington, N., Jumel, K., Ilium, L., Smith, A., Harding, S.E., Correlation of SEC/MALLS with ultracentrifuge and viscometric data for chitosans (2003) Eur Biophys J, 32, pp. 457-464; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res, 66 A (2), pp. 247-259; Andrade, J.D., Smith, L.M., Gregonis, D.E., The contact angle and interface energetics (1997) Physical Chemistry of Surfaces, pp. 249-292. , Adamson AW, Gast AP, editors. New York: John Wiley & Sons;; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., Attachment of cultured human bone cells to novel polymers (1999) J Biomed Mater Res, 44 (1), pp. 1-11; Lebaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: Functional applications in orthopedic materials (2000) Tissue Eng, 6 (2), pp. 85-103; Massia, S.P., Hubbell, J.A., An RGD spacing of 440 run is sufficient for integrin alpha-V-beta-3- mediated fibroblast spreading and 140 nm for focal contact and stress fiber formation (1991) J Cell Biol, 114 (5), pp. 1089-1100; Verrier, S., Fallu, S., Bareille, R., Jonczyk, A., Meyer, J., Dard, M., Amedee, J., Function of linear and cyclic RGD-containing peptides in osteoprogenitor cells adhesion process (2002) Biomaterials, 23 (2), pp. 585-596; Gronthos, S., Sirnmons, P.J., Graves, S.E., Robey, P.G., Integrin-mediated interactions between human bone marrow stromal precursor cells and the extracellular matrix (2001) Bone, 28 (2), pp. 174-181; Webb, K., Hlady, V., Tresco, P.A., Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces (2000) J Biomed Mater Res, 49 (3), pp. 362-368; Stein, G.S., Lian, J.B., Stein, J.L., Wijnen, A.J., Frenkel, B., Montecino, M., Mechanisms regulating osteoblast proliferation and differentiation (1996) Principles of Bone Biology, pp. 69-86. , Bilezikian JP, Raisz LG, Rodan GA, editors. San Diego: Academic Press; Aubin, J.E., Liu, F., The osteoblast lineage (1996) Principles of Bone Biology, pp. 51-67. , Bilezikian JP, Raisz LG, Rodan GA, editors. San Diego: Academic Press; Moursi, A.M., Globus, R.K., Damsky, C.H., Interactions between integrin receptors and fibronectin are required for calvarial osteoblast differentiation in vitro (1997) J Cell Sci, 110, pp. 2187-2196; Stephansson, S.N., Byers, B.A., Garcia, A.J., Enhanced expression of the osteoblastic phenotype on substrates that modulate fibronectin conformation and integrin receptor binding (2002) Biomaterials, 23 (12), pp. 2527-2534
Keywords: Acetylation; Adhesion; Adsorption; animal cell; Animals; article; artificial membrane; binding affinity; binding competition; Bone; bone development; bone marrow cell; Bone Marrow Cells; Bone marrow stomal cells; Bone marrow stromal cells; cell adhesion; cell anchorage; Cell culture; cell differentiation; Cell membranes; cell migration; cell proliferation; Cell Shape; cell spreading; chitosan; Coated Materials, Biocompatible; controlled study; cytoskeleton; Degree of acetylation; Fibronectin; Fibronectins; male; materials testing; morphology; nonhuman; polystyrene; Proteins; rat; Rats; Rats, Wistar; roughness; stroma cell; Stromal Cells; Surface Properties; surface property; Tissue culture; wettability

Recombinant glucocerebrosidase uptake by Gaucher disease human osteoblast culture model - Lamghari, M.; Barrias, C.C.; Sá Miranda, C.; Barbosa, M.A. (Blood Cells, Molecules, and DiseasesBlood Cells Mol. Dis., 2005)
Bone lesions are a major cause of morbidity in Gaucher disease (GD) type I. Enzyme replacement therapy (ERT) has been successful in treating many symptoms of type I GD but skeletal response lags behind. Local exogenous glucocerebrosidase supplementation in bone lesions via a drug delivery system may overcome this limitation. Although local enzyme supplementation aims to target lipid-engorged macrophages (Gaucher Cells) in bone compartment, enzyme uptake by osteoblasts is not excluded. To investigate the ability of human osteoblasts to internalize recombinant glucocerebrosidase (rGCR), we have used an artificial GD human osteoblasts cell culture system. MG63 human osteoblasts were treated with conduritol B epoxide (CBE) to induce complete and prolonged inhibition of endogenous glucocerebrosidase activity of cells. rGCR uptake by glucocerebrosidase-inactivated osteoblasts was examined using 125I-radiolabelling, Western blot analysis and measurement of glucocerebrosidase activity. Analysis of radiolabeled enzyme uptake by CBE treated osteoblasts showed 67.9% of internalized protein in cell extract. Enzyme internalization was also observed by Western blot analysis where the amount of mature form of glucocerebrosidase protein recognized by the glucocerebrosidase antibody was increased following the administrations of rGCR. Moreover, enzymatic activity measurement showed 23.9% of glucocerebrosidase activity of control cells. The rGCR internalization by MG63 osteoblast seems to be partially mediated by mannose receptors. These data provide evidence that MG63 human osteoblasts are able to internalize rGCR. © 2005 Elsevier Inc. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BCMDFdoi: 10.1016/j.bcmd.2005.07.009PubMed ID: 16125984Language of Original Document: EnglishCorrespondence Address: Lamghari, M.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, R. Campo Alegre 823, 4150-180 Porto, Portugal; email: lamghari@ineb.up.ptChemicals/CAS: conduritol b epoxide, 6090-95-5; imiglucerase, 154248-97-2; iodine 125, 14158-31-7, 22822-81-7; conduritol epoxide, 6090-95-5; Glucosylceramidase, EC 3.2.1.45; Inositol, 6917-35-7; Recombinant ProteinsTradenames: cerezyme, GenzymeManufacturers: GenzymeReferences: Beutler, E., Grabowski, G., Gaucher disease (1995) The Metabolic and Molecular Bases of Inherited Disease, 2, pp. 2641-2661. , C.R. Scriber A.L. Beaudet W.S. Sly 7th ed. McGraw-Hill New York, NY;Beutler, E., Enzyme replacement in Gaucher disease (2004) PLoS Med., 1 (2), p. 21; Elstein, D., Itzchaki, M., Mankin, H., Skeletal involvement in Gaucher's disease (1997) Ballière's Clin. Haematol., 10 (4), pp. 793-815; Wenstrup, R.J., Roca-Espiau, M., Weinreb, N.J., Bembi, B., Skeletal aspects of Gaucher disease: A review (2002) Br. J. Radiol., 75 (1 SUPPL.), pp. 2-A12; Barranger, J.A., O'Rourke, E., Lessons learned from the development of enzyme therapy for Gaucher disease (2001) J. Inherited Metab. Dis., 24 (2 SUPPL.), pp. 89-96; Zimran, A., Elstein, D., Levy-Lahad, E., Zevin, S., Hadas-Halpern, I., Bar-Ziv, Y., Foldes, J., Abrahamov, A., Replacement therapy with imiglucerase for type 1 Gaucher's disease (1995) Lancet, 345 (8963), pp. 1479-1480; Barton, N.W., Brady, R.O., Dambrosia, J.M., Di Bisceglie, A.M., Doppelt, S.H., Hill, S.C., Mankin, H.J., Argoff, C.E., Replacement therapy for inherited enzyme deficiency-macrophage-targeted glucocerebrosidase for Gaucher's disease (1991) N. Engl. J. Med., 324 (21), pp. 1464-1470; Barton, N.W., Furbish, F.S., Murray, G.J., Garfield, M., Brady, R.O., Therapeutic response to intravenous infusions of glucocerebrosidase in a patient with Gaucher disease (1990) Proc. Natl. Acad. Sci. U. S. A., 87 (5), pp. 1913-1916; Friedman, B., Vaddi, K., Preston, C., Mahon, E., Cataldo, J.R., McPherson, J.M., A comparison of the pharmacological properties of carbohydrate remodeled recombinant and placental-derived beta-glucocerebrosidase: Implications for clinical efficacy in treatment of Gaucher disease (1999) Blood, 93, pp. 2807-2816; Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev., 12 (2), pp. 115-133; Samuel, R., Katz, K., Papapoulos, S.E., Yosipovitch, Z., Zaizov, R., Liberman, U.A., Aminohydroxy propylidene bisphosphonate (APD) treatment improves the clinical skeletal manifestations of Gaucher's disease (1994) Pediatrics, 94 (3), pp. 385-389; Shiffmann, R., Mankin, H., Dambrosia, J.M., Xavier, R.J., Kreps, C., Hills, S.C., Barton, N.W., Rosenthal, D.I., Decreased bone density in splenectomized Gaucher patients receiving enzyme replacement therapy (2002) Blood Cells Mol. Dis., 28, pp. 288-296; (1993) Iodine-125, a Guide to Radioiodination, p. 64. , Amersham Life Science; Barrias, C.C., Martins, M.C.L., Sá Miranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: Effect of surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; Laemmli, U.K., (1970) Nature, 227, pp. 680-685; Sá Miranda, M.C., Aerts, J.M., Pinto, R., Fontes, A., Lacerda, L.W., Van Weely, S., Barranger, J., Tager, J.M., Activity of glucocerebrosidase in extracts of different cell types from type 1 Gaucher disease patients (1990) Clin. Genet., 38, pp. 218-227; Barrias, C.C., Lamghari, M., Granja, P.L., Sá Miranda, C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localised delivery of a therapeutic enzyme (2005) J. Biomed. Mater. Res.; Barrias, C.C., Ribeiro, C.C., Lamghari, M., Sá Miranda, C., Barbosa, M.A., Proliferation, activity, and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) J. Biomed. Mater. Res., 72 A (1), pp. 57-66; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25 (18), pp. 4363-4373; Das, P.K., Murray, G.J., Gal, A.E., Barranger, J.A., Glucocerebrosidase deficiency and lysosomal storage of glucocerebroside induced in cultured macrophages (1987) Exp. Cell Res., 168 (2), pp. 463-474; Pelled, D., Shogomori, H., Futerman, A.H., The increased sensitivity of neurons with elevated glucocerebroside to neurotoxic agents can be reversed by imiglucerase (2000) J. Inherited Metab. Dis., 23 (2), pp. 175-184; Hanley, K., Jiang, Y., Holleran, W.M., Elias, P.M., Williams, M.L., Feingold, K.R., Glucosylceramide metabolism is regulated during normal and hormonally stimulated epidermal barrier development in the rat (1997) J. Lipid Res., 38 (3), pp. 576-584; Marshall, J., McEachern, K.A., Kyros, J.A., Nietupski, J.B., Budzinski, T., Ziegler, R.J., Yew, N.S., Cheng, S.H., Demonstration of feasibility of in vivo gene therapy for Gaucher disease using a chemically induced mouse model (2002) Mol. Ther., 6 (2), pp. 179-189; Mistry, P.K., Wraight, E.P., Cox, T.M., Therapeutic delivery of proteins to macrophages: Implications for treatment of Gaucher's disease (1996) Lancet, 348 (9041), pp. 1555-1559; Xu, Y.H., Ponce, E., Sun, Y., Leonova, T., Bove, K., Witte, D., Grabowski, G.A., Turnover and distribution of intravenously administered mannose-terminated human acid beta-glucosidase in murine and human tissues (1996) Pediatr. Res., 39 (2), pp. 313-322; Beutler, E., Kuhl, W., Vaughan, L.M., Failure of alglucerase infused into Gaucher disease patients to localize in marrow macrophages (1995) Mol. Med., 1, pp. 320-324; Sato, Y., Beutler, E., Binding, internalization, and degradation of mannose-terminated glucocerebrosidase by macrophages (1993) J. Clin. Invest., 91, pp. 1909-1917; Schueler, U., Kaneski, C., Murray, G., Sandhoff, K., Brady, R.O., Uptake of mannose-terminal glucocerebrosidase in cultured human cholinergic and dopaminergic neuron cell lines (2002) Neurochem. Res., 27 (4), pp. 325-330; Furbish, F.S., Steer, C.J., Barranger, J.A., Jones, E.A., Brady, R.O., The uptake of native and desialylated glucocerebrosidase by rat hepatocytes and Kupffer cells (1978) Biochem. Biophys. Res. Commun., 81, pp. 1047-1053; Furbish, F.S., Steer, C.J., Krett, N.L., Barranger, J.A., Uptake and distribution of placental glucocerebrosidase in rat hepatic cells and effects of sequential deglycosylation (1981) Biochim. Biophys. Acta, 673, pp. 425-434; East, L., Isacke, C.M., The mannose receptor family (2002) Biochim. Biophys. Acta., 1572, pp. 364-386; East, L., Rushton, S., Taylor, M.E., Isack, C.M., Characterization of sugar binding by the mannose receptor family member, Endo180 (2002) J. Biol. Chem., 277 (52), pp. 50469-50475; Engelholm, L.H., Nielsen, B.S., Netzel-Arnett, S., Solberg, H., Chen, X.D., Lopez Garcia, J.M., Lopez-Otin, C., Bugge, T.H., The urokinase plasminogen activator receptor-associated protein/endo180 is coexpressed with its interaction partners urokinase plasminogen activator receptor and matrix metalloprotease-13 during osteogenesis (2001) Lab. Invest., 81, pp. 1403-1414; Bailey, L., Wienke, D., Howard, M., Knauper, V., Isacke, C.M., Murphy, G., Investigation of the role of Endo180/urokinase-type plasminogen activator receptor-associated protein as a collagenase 3 (matrix metalloproteinase 13) receptor (2002) Biochem. J., 1 (363 PART 1), pp. 67-72
Keywords: article; Cell culture; cell extract; Cells, Cultured; conduritol b epoxide; controlled study; drug activity; drug uptake; enzyme activity; enzyme antibody; Enzyme inhibition; Enzyme uptake; epoxide; Gaucher disease; Glucocerebrosidase; Glucosylceramidase; human; human cell; Humans; imiglucerase; Inositol; internalization; iodine 125; isotope labeling; mannose receptor; osteoblast; Osteoblasts; priority journal; Recombinant Proteins; unclassified drug; Western blotting

Segmentation of ultrasonic images of the carotid - Rocha, R.; Campilho, A.; Silva, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
A new algorithm for an effective and automatic segmentation of the carotid wall in ultrasonic images is proposed. It combines the speed of thresholding algorithms with the accuracy, flexibility and robustness of a successful geometric active contour model which incorporates an optimal image segmentation model in a level set framework. Due to the multiphase nature of these images, a sequential minimum cross entropy thresholding is used to get a first approximation of the segments, reducing the problem to a two phase segmentation. This thresholding solution is then used as a starting point for a two phase piecewise constant version of a geometric active contour model to reduce noise, smooth contours, improve their position accuracy and close eventual gaps in the carotid wall. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 67124Export Date: 21 November 2012Source: Scopusdoi: 10.1007/11559573_115Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Instituto de Engenharia Biomédica, Laboratório de Sinai e Imagem Biomédica, Porto, PortugalReferences: Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24, pp. 757-777;Sonka, M., Liang, W., Stefancik, R., Stolpen, A., (2000) Handbook of Medical Imaging: Medical Image Processing and Analysis, 2. , SPIE; Christodoulou, C.I., Pattichis, C.S., Pantziaris, M., Nicolaides, A., Texture based classification of atherosclerotic carotid plaques (2003) IEEE Trans. Med. Imaging, 22, pp. 902-912; Barratt, D., Ariff, B., Humphries, K., Thom, S., Hughes, A., Reconstruction and quantification of the carotid artery bifurcation from 3-d ultrasound images (2004) IEEE Trans. Med. Imaging, 23, pp. 567-583; Li, C., Lee, C., Minimum cross entropy thresholding (1993) Pattern Recogn, 26, pp. 617-625; Brink, A., Pendock, N., Minimum cross-entropy threshold selection (1996) Pattern Recogn., 29, pp. 179-188; Chan, T., Vese, L., Active contours without edges (2001) IEEE Trans. on Image Processing, 10, pp. 266-277; Vese, L.A., Chan, T.F., A multiphase level set framework for image segmentation using the Mumford and Shah model (2002) Int. J. Comput. Vision, 50, pp. 271-293; Touboul, P., Prati, P., Abd, V., Adrai, P.Y.S., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertension, 10, pp. 37-41; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imaging, 19, pp. 127-142; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clinical Physiology, 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Sandrock, M., Pu, Q., Burkhardt, H., Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound B-mode images using snakes (1999) International Conference on Image Analysis and Processing, pp. 452-457. , B. Werner; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Computer Methods and Programs in Biomedicine, 67, pp. 27-37; Baillard, C., Barillot, C., Bouthemy, P., Robust adaptive segmentation of 3D medical images with level sets (2000) Technical Report, , IRISA, Campus Universitaire de Beaulieu, Prance; Tsai, A., Yezzi III, A.J., W., W.M., Tempany, C., Tucker, D., Fan, A., Grimson, W.E.L., Willsky, A.S., A shape-based approach to the segmentation of medical imagery using level sets (2003) IEEE Trans. Med. Imaging, 22, pp. 137-154; Perona, P., Malik, J., Scale-space and edge detection using anisotropic diffusion (1990) IEEE Trans. Pattern Anal. Mach. Intell., 12, pp. 629-639; Sethian, J.A., (1999) Level Set Methods and Fast Marching Methods, , Cambridge University Press; Osher, S., Fedkiw, R., (2003) Level Set Methods and Dynamic Implicit Surfaces, , Springer-Verlag. New York; Mumford, D., Shah, J., Optimal approximations by piecewise smooth functions and associated variational problems (1989) Communications on Pure and Applied Mathematics, 42, pp. 577-685; Gao, S., Bui, T.D., Image segmentation and selective smoothing by using the Mumford-Shah model (2005) IEEE Trans. on Image Processing, , To be published in
Keywords: Active contour model; Algorithms; Approximation theory; Carotid wall; Image segmentation; Image segmentation model; Mathematical models; Optimization; Ultrasonic imaging

Spectral methods in image segmentation: A combined approach - Monteiro, F.C.; Campilho, A.C. (Lecture Notes in Computer ScienceLect. Notes Comput. Sci., 2005)
Grouping and segmentation of images remains a challenging problem in computer vision. Recently, a number of authors have demonstrated a good performance on this task using spectral methods that are based on the eigensolution of a similarity matrix. In this paper, we implement a variation of the existing methods that combines aspects from several of the best-known eigenvector segmentation algorithms to produce a discrete optimal solution of the relaxed continuous eigensolution. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 65649Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Monteiro, F.C.; INEB - Instituto de Engenharia Biomédica, Campus de Santa Apolónia, Apartado 134, 5301-857 Bragança, Portugal; email: monteiro@ipb.ptReferences: Fowlkes, C., Belongie, S., Chung, F., Malik, J., Spectral grouping using nyström method (2004) Trans. on Pattern Analysis and Machine Intelligence, 26 (2), pp. 214-225;Malik, J., Belongie, S., Leung, T., Shi, T., Contour and texture analysis for image segmentation (2001) International Journal of Computer Vision, 43 (1), pp. 7-27; Martin, D., Fowlkes, C., Tal, D., Malik, J., A database of human segmented natural images and its application to evaluating segmentation algorithms and measuring ecological statistics (2001) IEEE Int. Conf. on Computer Vision, 2, pp. 416-424; Meila, M., Shi, J., Learning segmentation by random walks (2000) Neural Information Processing Systems, pp. 873-879; Ng, A., Jordan, M., Weiss, Y., On spectral clustering: Analysis and an algorithm (2002) Advances in Neural Information Processing Systems, 14, pp. 849-856; Scott, D.S., Solving sparse symmetric generalized eigenvalue without factorization (1981) SIAM Journal of Numerical Analisys, 18, pp. 102-110. , http://www.netlib.org/laso/snlaso.f; Scott, G.L., Longuet-Higgins, H.C., Feature grouping by "relocalisation" of eigenvectors of the proximity matrix (1990) Proc. British Machine Vision Conf., pp. 103-108; Shi, J., Malik, J., Normalized cuts and image segmentation (2000) IEEE Trans. on Pattern Analysis and Machine Intelligence, 22 (8), pp. 888-905; Weiss, Y., Segmentation using eigenvectors: A unifying view (1999) International Conference on Computer Vision, pp. 975-982; Wertheimer, M., Laws of organization in perceptual forms (1938) A Sourcebook of Gestalt Psychology, pp. 71-88. , W. B. Ellis Editor; Wu, Z., Leahy, R., An optimal graph theoretic approach to data clustering: Theory and its application to image segmentation (1993) IEEE Trans. on Pattern Analysis and Machine Intelligence, 15, pp. 1101-1113; Yu, S., Shi, J., Multiclass spectral clustering (2003) International Conference on Computer Vision, pp. 313-319. , Nice, France
Keywords: Algorithms; Computer vision; Discrete optimal solution; Eigensolution; Eigenvalues and eigenfunctions; Image segmentation; Matrix algebra; Problem solving; Similarity matrix; Spectral methods

Synthesis and characterization of new injectable and degradable dextran-based hydrogels - Maia, J.; Ferreira, L.; Carvalho, R.; Ramos, M.A.; Gil, M.H. (PolymerPolymer, 2005)
Injectable and degradable hydrogels are very interesting networks for drug delivery and cell transplantation applications since they can be administered in the human body in a minimally invasive way. In most cases, the crosslinking reaction occurs by photopolymerisation or free radical polymerisation; however, the use of chemical initiators may promote cell death. In the current work, injectable and degradable dextran-based hydrogels were prepared without the use of initiators. Dextran, a natural glucose-containing polysaccharide, was oxidized with sodium periodate (dexOx) and the derivatives characterized by NMR and FTIR spectroscopy's as well as by colorimetric techniques. The oxidized derivatives were crosslinked with adipic acid dihydrazide (AAD), forming a gel within 2-4 min. The obtained hydrogels were characterized by their mechanical properties, swelling and degradation behavior under physiologic conditions. In addition, the hydrogel interior morphology as well as porous structure was evaluated by scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP). MIP analysis showed that dexOx hydrogels crosslinked with 10% of AAD were macroporous with pore sizes ranging from 0.32 to 0.08 μm. As expected, the average pore size increased during hydrogel degradation as confirmed by SEM and MIP studies. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 49Export Date: 21 November 2012Source: ScopusCODEN: POLMAdoi: 10.1016/j.polymer.2005.07.089Language of Original Document: EnglishCorrespondence Address: Maia, J.; Departamento de Engenharia Química, Universidade de Coimbra, Pinhal de Marrocos, 3030 Coimbra, Portugal; email: joao.rm.silva@networkcontacto.comReferences: Ferreira, L., Carvalho, R., Gil, M.H., Dordick, J.S., (2002) Biomacromolecules, 3, p. 333;Ferreira, L., Gil, M.H., Dordick, J.S., (2002) Biomaterials, 23, p. 3957; Ferreira, L., Rafael, A., Lamghari, M., Barbosa, M.A., Gil, M.H., Cabrita, A.M.S., (2004) J Biomed Mater Res, 68, p. 584; Lee, K.Y., Mooney, D.J., (2001) Chem Rev, 101 (7), p. 1869; Peppas, N.A., Bures, P., Leobandung, W., Ichikawa, H., (2000) Eur J Pharma Biopharm, 50, p. 27; Wong, W.H., Mooney, D.J., (1997) Synthetic Biodegradable Polymer Scaffolds, pp. 49-82. , A. Atala D.J. Mooney Birkhäuser Boston; Mehvar, R., (2000) J Controlled Release, 69, p. 1; Nguyen, K.T., West, J.L., (2002) Biomaterials, 23, p. 4307; Liu, V.A., Bhatia, S.N., (2002) Biomed Microdevices, 4 (4), p. 257; Williams, C.G., Malik, A.N., Kim, T.K., Manson, P.N., Elisseeff, J.H., (2005) Biomaterials, 26, p. 1211; Bouhadir, K.H., Hausman, D.S., Mooney, D.J., (1999) Polymer, 40, p. 3575; Lee, K.Y., Alsberg, E., Mooney, D.J., (2001) J Biomed Mater Res, 56, p. 228; Lee, K.Y., Bouhadir, K.M., Mooney, D.J., (2000) Macromolecules, 33, p. 97; Kim, S.-H., Chu, C.C., (2000) J Biomed Mater Res, Appl Biomater, 53, p. 258; Meyvis, T., De Smedt, S., Stubbe, B., Hennink, W.E., Demeester, J., (2001) Pharm Res, 18 (11), p. 1593; Dziubla, T.D., Torjman, M.C., Joseph, J.I., Murphy-Tatum, M., Lowman, A.M., (2001) Biomaterials, 22, p. 2893; Jen, A.C., Wake, M.C., Mikos, A.G., (1996) Biotechnol Bioeng, 50, p. 357; Schneerson, R., Barrera, O., Sutton, A., Robbis, J.B., (1980) J Exp Med, 152, p. 361; Jia, X., Burdick, J.A., Kobler, J., Clifton, R.J., Rosowski, J.J., Zeitels, S.M., (2004) Macromolecules, 37, p. 3239; Edwards-Lévy, F., Andry, M.C., Lévy, M.C., (1993) Int J Pharm, 96, p. 85; Meyvis, T.K.L., De Smedt, S.C., Demeester, J., Hennin, W.E., (1999) J Rheol, 43, p. 933; Behravesh, E., Jo, S., Zygourakis, K., Mikos, A.G., (2002) Biomacromolecules, 3, p. 374; Washburn, E.W., (1921) Proc Natl Acad Sci, 7, p. 115; Ishak, M.F., Painter, T.J., (1978) Carbohyd Res, 64, p. 189; Tiziani, S., Sussich, F., Cesáro, A., (2003) Carbohyd Res, 338, p. 1083; Van Dijk-Wolthuis, W.N.E., Franssen, O., Talsma, H., Van Steenbergen, M.J., Kettenes-Van Den Bosch, J.J., Hennink, W.E., (1995) Macromolecules, 28, p. 6317; Yu, R.J., Bishop, C.T., (1967) Can J Chem, 45, p. 2195; Domb, A.J., Linden, G., Polacheck, I., Benita, S., (1996) J Polym Sci, Part A: Polym Chem, 34, p. 1229; Pavia, D.L., Lampma, G.M., Kriz, G.S., (1996) Introduction to Spectroscopy, , 2nd ed Saunders College Publishing London; Vervoort, L., Vinckier, I., Moldenaers, P., Van Den Mooter, G., Augustijns, P., Kinget, R., (1999) J Pharm Sci, 88, p. 209; Smedt, S.C.D., Lauwers, A., Demeester, J., Van Steenbergen, M.J., Hennink, W.E., Roefs, S.P.F.M., (1995) Macromolecules, 28, p. 5082; Bell, C.L., Peppas, N.A., (1995) Adv Polym Sci, 122, p. 125; Van Dijk-Wolthuis, W.N.E., Hoogeboom, J.A.M., Van Steenbergen, M.J., Tsang, S.K.Y., Hennink, W.E., (1997) Macromolecules, 30, p. 4639; Dawlee, S., Sugandhi, A., Balakrishnan, B., Labarre, D., Jayakrishnan, A., (2005) Biomacromolecules, 6, p. 2040; Peppas, N.A., Hydrogels (1996) Biomaterials Science: An Introduction to Materials in Medicine, p. 60. , B.D. Ratner A.S. Hoffman F.J. Schoen J.E. Lemons Academic Press London; Pirard, R., Rigacci, A., Maréchal, J.C., Quenard, D., Chevalier, B., Achard, P., (2003) Polymer, 44, p. 4881; Ferreira, L., Gil, M.H., Cabrita, A.M.S., Dordick, J.S., (2005) Biomaterials, 26, p. 4707
Keywords: Cell Death; Cell transplantation; Colorimetry; Crosslinking; Degradation; Drug delivery; Drug dosage; Fourier transform infrared spectroscopy; Free radical polymerization; hydrogel; Hydrogels; Mercury intrusion porosimetry (MIP); morphology; Nuclear magnetic resonance spectroscopy; Photopolymerization; Polysaccharides; Pore size; Porosimeters; Scanning electron microscopy; Synthesis (chemical)

TiO 2 type influences fibronectin adsorption - Sousa, S.R.; Moradas-Ferreira, P.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2005)
Human fibronectin (FN) plays a key role in the biointegration of implants as the success depends on adsorption of proteins like FN [1]. Indeed FN can be an intermediary between the biomaterial surface and cells. The adsorption of human fibronectin (FN) on commercially pure titanium with a titanium oxide layer formed in a H 2O 2 solution (TiO 2 cp) and TiO 2 sputtered on Si (TiO 2 sp) was studied. Adsorption isotherms and the work of adhesion were assessed by wettability studies, X-ray photoelectron spectroscopy (XPS), and by radiolabelling of FN with 125I, 125I-FN. Exchangeability of bound FN by free FN, was also evaluated by the radiolabelling technique. Contact angle determinations have shown that FN displays higher affinity for the TiO 2 cp surface than for the TiO 2 sp. As expected from the surface free energy values, the work of adhesion of FN is higher for the TiO 2 cp substrate, the more hydrophilic one, and lower for the TiO 2 sp substrate, the more hydrophobic one. The adsorption isotherms were evaluated by two different techniques: radiolabelling of FN ( 125I-FN) and XPS. TiO 2 cp adsorbs more FN than the TiO 2 sp surfaces as shown by the radiolabelling data. FN molecules are also more strongly attached to the former surface as indicated by the work of adhesion and by the exchangeability studies. Results using 125I-FN also suggests that FN adsorbs as a multilayer for FN concentrations in solution higher than 100 μg/mL. © 2005 Springer Science + Business Media, Inc.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-005-4725-4Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Instituto de Engenharia Biomédica, Lab. Biomateriais, R. do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ssousa@ibmc.up.ptChemicals/CAS: fibronectin, 86088-83-7; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; titanium, 7440-32-6; hydrogen peroxide, 7722-84-1; iodine 125, 14158-31-7, 22822-81-7; Fibronectins; Solutions; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: Horbett, T.A., (1994) Colloids and Surfaces B: Biointerfaces, 2, p. 225;Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J Biomed Mater Res., 75 A, p. 387; Johnson, K.J., Sage, H., Briscoe, G., Erickson, H.P., (1999) J. Biol. Chem., 274, p. 15473; Bergkvist, M., Carlsson, J., Oscarsson, S., (2003) J. Biomed. Mater. Res. Part A., 64 A, p. 349; Ugarova, T.P., Zamarron, C., Veklich, Y., Bowditch, R.D., Ginsberg, M.H., Weisel, J.W., Plow, E.F., (1995) Biochemistry, 34, p. 4457; Sukenik, C.N., Balachander, N., Culp, L.A., Lewandowska, K., Merritt, K., (1990) J. Biomed. Mater. Res., 24, p. 1307; Sousa, S.R., Moradas- Ferreira, P., Melo, L.V., Saramago, B., Barbosa, M.A., (2004) Langmuir, 20, p. 9745; Gehanno, V., Freitas, P.P., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Soares, J.C., Silva, M.F., (1999) IEEE Trans. Magn., 35, p. 4361; (2003) Iodine-125, A Guide to Radioiodination Techniques - Amersham Life Science, p. 64. , Amersham International plc, Amersham Place, Little Chalfont, Bucks, HP7 9NA, England, 199; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, p. 45; Yu, X.J., Brash, J.L., (1993) Test Procedures for the Blood Compatibility of Biomaterials, Dordrecht, p. 287. , edited by S. Dawids (Kluwer Academic Publishers, Dordrecht); Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Analytical Biochemistry, 150, p. 76; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interface Sci., 95, p. 308; Auditore, A., Satriano, C., Coscia, U., Ambrosone, G., Parisi, V., Marletta, G., (2002) Biomolecular Engineering, 19, p. 85; Miller, R., Treppo, S., Voigt, A., Zingg, W., Neumann, A.W., (1993) Colloids and Surfaces, 69, p. 203; Serro, A.P.V., Fernandes, A.C., Saramago, B.D.V., (1997) Colloids and Surfaces A-Physicochemical and Engineering Aspects, 125, p. 209; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., (1997) Langmuir, 13, p. 3404; Matsuura, T., Hosokawa, R., Okamoto, K., Kimoto, T., Akagawa, Y., (2000) Biomaterials, 21, p. 1121; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, p. 3105; Do Serro, A., Fernandes, A.C., Saramago, B.D.V., Norde, W., (1999) J. Biomed. Mater. Res., 46, p. 376; Norde, W., Anusiem, A.C.I., (1992) Colloids and Surfaces, 66, p. 73; Rouxhet, L., Duhoux, F., Borecky, O., Legras, R., Schneider, Y.J., (1998) Journal of Biomaterials Science-Polymer Edition, 9, p. 1279; Norde, W., (1986) Advances in Colloid and Interface Science, 25, p. 267; Tamada, Y., Ikada, Y., (1993) J. Colloid Interface Sci., 155, p. 334
Keywords: Adsorption; adsorption kinetics; article; binding affinity; Biointegration; Biomaterials; Cells; chemistry; conference paper; Contact angles; Fibronectin; Fibronectins; human; Human fibronectin (FN); Humans; hydrogen peroxide; hydrophilicity; hydrophobicity; Implants (surgical); iodine 125; isotherm; Isotherms; isotope labeling; physical chemistry; priority journal; protein binding; Proteins; Radiolabelling; solution and solubility; Solutions; surface property; Titanium; Titanium dioxide; wettability; X ray photoelectron spectroscopy

Automatic delimitation of lung fields on chest radiographs - Mendonça, A.M.; Da Silva, J.A.; Campilho, A. (2004 2nd IEEE International Symposium on Biomedical Imaging: Macro to NanoIEEE Int. Symp. Biomed. Imaging Macro Nano, 2004)
The purpose of the research herein presented is the automatic delimitation of lung fields in posterior-anterior digital chest radiographs. In a computer-aided diagnosis system the precise location of the lungs is important as it allows the reduction of the region under analysis, decreasing the computation time and facilitating data compression. Furthermore, it allows the delimitation of the search area, easing the selective tuning of the abnormalities detection algorithms. The results produced by the automatic method were validated by comparison with manual contours traced by experienced radiologists. Two programs with friendly interfaces were developed for this purpose. © 2004 IEEE.
Conference code: 64593Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Mendonça, A.M.; Inst. de Engenharia Biomédica, Lab. de Sinai e Imagem Biomedica, Campus da FEUP, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, PortugalReferences: Tsujii, O., Freedman, M., Mun, S., Automated segmentation of anatomic regions in chest radiographs using an adaptive-sized hybrid neural network (1998) Medical Physics, 25, pp. 998-1007;Armato III, S., Giger, M., MacMahon, H., Computerized detection of abnormal asymetry in digital lateral chest radiographs (1994) Medical Physics, 21, pp. 1761-1768; Armato III, S., Giger, M., Ashizawa, K., MacMahon, H., Automated lung segmentation in digital lateral chest radiographs (1998) Medical Physics, 25, pp. 1507-1520; Carrascal, F., Carreira, J., Souto, M., Automatic calculation of total lung capacity from automatically traced lung boundaries in posterior-anterior and lateral digital chest radiographs (1998) Medical Physics, 25, pp. 1118-1131; Ginneken, B., Romeny, B., Automatic segmentation of lung fields in chest radiographs (2000) Medical Physics, 27, pp. 2445-2455; Li, L., Zheng, Y., Kallergi, M., Clark, R., Improved method for automatic identification of lung regions on chest radiographs (2001) Academic Radiology, 8, pp. 629-638; Monteiro, M., Mendonça, A.M., Campilho, A., Lung field detection on chest radiographs (2002) Proceedings of VIIP02, IASTED International Conference on Visualization, Imaging and Image Processing, pp. 367-372. , J. Villanueva (eds.), Spain Sponsors: IEEE
Keywords: Algorithms; Chest radiographs; Computer aided diagnosis; Contour detection; Data compression; Edge detection; Image segmentation; Lung fields; Pulmonary diseases; Radiography; X ray analysis; X ray imaging

Automatic lane and band detection in images of thin layer chromatography - Sousa, A.V.; Aguiar, R.; Mendonca, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
This work aims at developing an automatic method for the analysis of TLC images for measuring a set of features that can be used for the characterization of the distinctive patterns that result from the separation of oligosaccharides contained in human urine. This paper describes the methods developed for the automatic detection of the lanes contained in TLC images, and for the automatic separation of bands for each detected lane. The extraction of quantitative information related with each band was accomplished with two methods: the EM expectation-maximization and nonlinear least squares trustregion algorithms. The results of these methods, as well as additional quantitative information related with each band, are also presented. © Springer-Verlag 2004.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Institute de Engenharia Biomédica, Rua Roberto Prias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Sewell, A., (1991) Urinary Oligosaccharides. Techniques in Diagnostic Human Biochemical Genetics, pp. 219-231. , Willey-Liss, Inc;Thomas, G., Disorders of Glycoprotein Degradation. α-Mannosidosis, β-Mannosidosis, Fucosidosis and Sialidosis, , Disorders of Glycoprotein Degradation (Chap. 140); Starr, C., Masada, R., Hague, C., Klock, J., Fluorophore-assisted Carbohydrate Electrophoresis in the Separation, Analysis, and Sequencing of Carbohydrates (1996) Journal of Chromatography A, 720, pp. 295-321; Klein, A., Lebreton, A., Lemoine, J., Périni, J., Roussel, P., Michalski, J., Identification of Urinary Oligosaccharides by Matrix-assisted Laser Desorption Ionization Time-of-flight Mass Spectrometry (1998) Clinical Chemistry, 44 (12), pp. 2422-2428; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from Incomplete Data via the em Algorithm (1977) Journal of the Royal Statistical Society, B, 39 (1), pp. 1-38; Schwedt, G., The Essential Guide to Analytical Chemistry, , John Wiley & Sons; Dennis, J., Nonlinear Least-squares, State of the Art in Numerical Analysis, , D. Jacobs Academic Press; Byrd, R., Schnabel, R., Shultz, G., Approximate Solution of the Trust Region Problem by Minimization over Two-Dimensional Subspaces (1988) Mathematical Programming, 40, pp. 247-263; Branch, M., Coleman, T., Li, Y., A Subspace, Interior, and Conjugate Gradient Method for Large-Scale Bound-Constrained Minimization Problems (1999) SIAM SISC, 21 (1), pp. 1-23; Nabney, I., Netlab Algorithms for Pattern Recognition (2003) Advances in Pattern Recognition, , Springer; Marques, J., Reconhecimento de Padrões, , Métodos Estatisticos e Neuronais, IST-Press; Machado, A., Campos, M., Siqueira, A., Carvalho, O., (1997) An Iterative Algorithm for Segmenting Lanes in Gel Electrophoresis Images;

Biocompatibility of chemoenzymatically derived dextran-acrylate hydrogels - Ferreira, L.; Rafael, A.; Lamghari, M.; Barbosa, M.A.; Gil, M.H.; Cabrita, A.M.S.; Dordick, J.S. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2004)
The biocompatibility of chemoenzymatically generated dextran-acrylate hydrogels has been evaluated in vitro, using human foreskin fibroblasts, and in vivo, by subcutaneous and intramuscular implantation in Wistar rats for up to 40 days. In vitro tests show that hydrogel extracts only minimally reduced (<10%) the mitochondrial metabolic activity of fibroblasts. Direct contact of the hydrogels with cells induced a cellular proliferation inhibition index (CPII) of 50-80%, compared with a control, whereas through indirect contact, the CPII values were <16%, suggesting that the high CPII values achieved in the direct assay test were likely due to mechanical stress or limitations in oxygen diffusion. Hence, the hydrogels were noncytotoxic. Moreover, cell-material interaction studies show that these hydrogels were nonadhesive. Finally, histologic evaluation of tissue response to subcutaneous and intramuscular implants showed acceptable levels of biocompatibility, as characterized by a normal cellular response and the absence of necrosis of the surrounding tissues of the implant. In the first 10 days, the foreign-body reaction in the intramuscular implantation was more severe than in subcutaneous implantation, becoming identical after 30 days. In both cases, dextran hydrogels did not show signs of degradation 6 weeks postimplantation and were surrounded by a thin fibrous capsule and some macrophages and giant cells. This response is typical with a number of nondegradable biocompatible materials. These results indicate that dextran hydrogels are biocompatible, and may have suitable applications as implantable long-term peptide/protein delivery systems or scaffolds for tissue engineering. © 2004 Wiley Periodicals, Inc.
Cited By (since 1996): 21Export Date: 21 November 2012Source: ScopusCODEN: JBMRCPubMed ID: 14762939Language of Original Document: EnglishCorrespondence Address: Dordick, J.S.; Department of Chemical Engineering, Rensselaer Polytechnic Institute, Troy, NY 12180, United States; email: dordick@rpi.eduChemicals/CAS: acrylic acid, 10344-93-1, 79-10-7; dextran, 87915-38-6, 9014-78-2; Acrylates; Biocompatible Materials; Dextrans, 9004-54-0; Enzymes; HydrogelsReferences: Ferreira, L., Gil, M.H., Dordick, J.S., Enzymatic synthesis of dextran-containing hydrogels (2002) Biomaterials, 23, pp. 3957-3967;Peppas, N.A., Bures, P., Leobandung, W., Ichikawa, H., Hydrogels in pharmaceutical formulations (2000) Eur J Pharm Biopharm, 50, pp. 27-46; Park, K., Park, H., Biocompatibility issues of implantable drug delivery systems (1996) Pharm Res, 13 (12), pp. 1770-1776; Novick, S.J., Dordick, J.S., Preparation of active and stable biocatalytic hydrogels for use in selective transformation (1998) Chem Mater, 10 (4), pp. 955-958; Letourneur, D., Machy, D., Pellé, A., Marcon-Bachari, E., Dángelo, G., Vogel, M., Chaubert, F., Michel, J.-B., Heparin and non-heparin-like dextrans differentially modulate endothelial cell proliferation: In vitro evaluation with soluble and crosslinked polysaccharide matrices (2002) J Biomed Mater Res, 60, pp. 94-100; Österberg, E., Bergström, K., Holmberg, K., Schuman, T.P., Riggs, J.A., Burns, N.L., Van Alstine, J.M., Harris, J.M., Protein-rejecting ability of surface-bound dextran in end-on and side-on configurations: Comparison to PEG (1995) J Biomed Mater Res, 29, pp. 741-747; Frazier, R.A., Matthijs, G., Davies, M.C., Roberts, C.J., Schacht, E., Tendler, S.J.B., Characterization of protein-resistant dextran monolayers (2000) Biomaterials, 21, pp. 957-966; Massia, S.P., Stark, J., Immobilized RGD peptides on surface-grafted dextran promote biospecific cell attachment (2001) J Biomed Mater Res, 56, pp. 390-399; Wong, W.H., Mooney, D.J., Synthesis and properties of biodegradable polymers used as synthetic matrices for tissue engineering (1997) Synthetic Biodegradable Polymer Scaffolds, p. 50. , Atala A, Mooney DJ, editors. Boston, MA: Birkhäuser; Lee, K.Y., Mooney, D.J., Hydrogels for tissue engineering (2001) Chem Rev, 101 (7), pp. 1869-1879; Hern, D.L., Hubbell, J.A., Incorporation of adhesion peptides into nonadhesive hydrogels useful for tissue resurfacing (1998) J Biomed Mater Res, 39, pp. 266-276; Mann, B.K., Gobin, A.S., Tsai, A.T., Schmedlen, R.H., West, J.L., Smooth muscle cell growth in photopolymerized hydrogels with cell adhesive and proteolytically degradable domains: Synthetic ECM analogs for tissue engineering (2001) Biomaterials, 22, pp. 3045-3051; De Groot, C.J., Van Luyn, M.J.A., Van Dijk-Wolthuis, W.N.E., Cadée, J.A., Plantinga, J.A., Den Otter, W., Hennink, W.E., In vitro biocompatibility of biodegradable dextran-based hydrogels tested with human fibroblasts (2001) Biomaterials, 22, pp. 1197-1203; Cadée, J.A., Luyn, M.J.A., Brouwer, L.A., Plantinga, J.A., Van Wachem, P.B., Groot, C.J., Otter, W., Hennink, W.E., In vivo biocompatibility of dextran-based hydrogels (2000) J Biomed Mater Res, 50, pp. 397-404; Anderson, J.M., In vivo biocompatibility of implantable delivery systems and biomaterials (1994) Eur J Pharm Biopharm, 40 (1), pp. 1-8; Anderson, J.M., Inflammation, wound healing, and the foreign body reaction response (1996) Biomaterials Science, pp. 165-173. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE, editors. New York: Academic Press; (1992) ISO 10993-5: Biological Evaluation of Medical Devices. Test for Cytotoxicity: In Vitro Methods, , Geneva, Switzerland: International Organization for Standardization; Pizzoferato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Bancroft, J.D., Stevens, A., (1996) Theory and Practice of Histological Techniques, pp. 99-211. , Edinburg: Churchill Livingstone; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Moreau, M.F., Chappard, D., Lesourd, M., Monthéard, J.P., Baslé, M.F., Free radicals and side products released during methylmethacrylate are cytotoxic for osteoblastic cells (1998) J Biomed Mater Res, 40, pp. 124-131; Black, J., The inflammatory response (1999) Biological Performance of Materials, p. 131. , Black J, editor. New York: Marcel Dekker; Murch, A.R., Grounds, M.D., Marshall, C.A., Papadimitriou, J.M., Direct evidence that inflammatory multinucleate giant cells form by fusion (1982) J Pathol, 137, pp. 177-180; Kuijpers, A.J., Wachem, P.B., Luyn, M.J.A., Plantinga, J.A., Engbers, G.H.M., Krijgsveld, J., Zaat, S.A.J., Feijen, J., In vivo compatibility and degradation of crosslinked gelatin gels incorporated in knitted Dacron (2000) J Biomed Mater Res, 51, pp. 136-145; Kuijpers, A.J., Van Wachem, P.B., Luyn, M.J.A., Brouwer, L.A., Engbers, G.H.M., Krijgsveld, J., Zaat, S.A.J., Feijen, J., In vitro and in vivo evaluation of gelatin-chondroitin sulphate hydrogels for controlled release of antibacterial proteins (2000) Biomaterials, 21, pp. 1763-1772; Hooper, K.A., Macon, N.D., Kohn, J., Comparative histological evaluation of new tyrosine-derived polymers and poly(L-lactic acid) as a function of polymer degradation (1998) J Biomed Mater Res, 41, pp. 443-454; Bos, R.R.M., Rozema, F.R., Boering, G., Nijenhuis, A.J., Pennings, A.J., Verwey, A.B., Nieuwenhuis, P., Jansen, H.W.B., Degradation of and tissue reaction to biodegradable poly(L-lactide) for use as internal fixation of fractures: A study in rats (1991) Biomaterials, 12, pp. 32-36; Nakamura, T., Veda, H., Tsuda, T., Li, Y.-H., Kiyotani, T., Inoue, M., Matsumoto, K., Shimizu, Y., Long-term implantation test and tumorigenicity of polyvinyl alcohol hydrogel plates (2001) J Biomed Mater Res, 56, pp. 289-296; Dziubla, T.D., Torjman, M.C., Joseph, J.I., Murphy-Tatum, M., Lowman, A.M., Evaluation of porous networks of poly(2-hydroxyethylmethacrylate) as interfacial drug delivery devices (2001) Biomaterials, 22, pp. 2893-2899; Spector, M., Lalor, P.A., In vivo assessment of tissue compatibility (1996) Biomaterials Science, pp. 220-228. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE, editors. New York: Academic Press
Keywords: Acrylates; acrylic acid; animal experiment; animal model; animal tissue; Animals; article; Biocatalytic polyester; Biocompatibility; Biocompatible Materials; Biodegradation, Environmental; Biodiversity; Biomaterials; cell adhesion; Cell Division; cell interaction; cell proliferation; Cells, Cultured; Coenzymes; controlled study; Cytotoxicity; dextran; dextran acrylate; dextran acrylate hydrogel; dextran hydrogel; Dextrans; drug delivery system; Enzymes; fibroblast; Fibroblasts; Fibrous capsules; foreign body reaction; Foreign-Body Reaction; giant cell; human; human cell; Humans; hydrogel; Hydrogels; implantation; Implants (surgical); Implants, Experimental; in vitro study; in vivo study; macrophage; male; materials testing; mechanical stress; Mechanical stresses; metabolism; Mitochondria; mitochondrial respiration; nonhuman; oxygen diffusion; prepuce; rat; Rats; Rats, Wistar; Tissue; Tissue engineering; unclassified drug

Biological Activity of Two Glass Ceramics in the Meta- and Pyrophosphate Region: A Comparative Study - Dias, A.G.; Costa, M.A.; Lopes, M.A.; Santos, J.D.; Fernandas, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Based upon the CaO-P 2O 5 glass system, two glass ceramics were prepared in the metaand pyrophosphate regions. The present work describes preliminary results concerning the biological activity of MK5B (45CaO-45P 2O 5-5MgO-5K20, in mol %) and MT13B (45CaO-37P 2O 55-5MgO-13TiO 2, in mol %) using MG63 osteoblast-like cells. Both materials supported cell growth and proliferation which increased with the incubation time. However, cell growth was significantly lower on seeded MK5B samples. SEM observation showed that cell adhesion and spreading were hampered on this material. Evident degradation of the material surface was observed with simultaneous cell proliferation and material precipitation. By contrast, MT13B presented a relatively stable surface throughout the culture time. Results suggest that the in vitro biological behaviour of MK5B and MT13B is related with differences in the degradation rates of the two materials during the culture time.
Conference code: 62053Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Dias, A.G.; Faculdade de Engenharia, Universidade do Porto, DEMM, Rua Dr. Roberta Frias, 4200 Porto, PortugalReferences: Dias, A.G., Lopes, M.A., Gibson, I., Santos, J.D., J. Non-Crystal. Solids, , in press;Dias, A.G., Lopes, M.A., Tsuru, K., Hayakawa, S., Santos, J.D., Osaka, A., Physiscs and Chemistry of Glasses, , in press; Dias, A.G., Lopes, M.A., Santos, J.D., Advance Materials Science, , in press; Rykke, M., Rolla, G., Sonju, T., (1988) Scand. J. Dent. Res., 96, pp. 517-522
Keywords: Adhesion; Biodegradable glass ceramics; Biodegradation; Bone; cell proliferation; Cells; Crystallization; Degradation; Glass ceramics; incubation time; MG63 osteoblast-like cells; Scanning electron microscopy; X ray diffraction

Bonelike®/PLGA hybrid materials for bone regeneration: In vivo evaluation - Oliveira, J.M.; Kawai, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D.; Afonso, A. (Materials Science ForumMater Sci Forum, 2004)
The biocompatibility and osteoconductive potential of Bonelike® and Bonelike®/PLGA hybrid materials were evaluated through subcutaneous and tibiae implantations for a 4 week period. Qualitative histology was performed to evaluate new bone formation and characterise bone-implant interface and results showed that Bonelike®/PLGA hybrid materials promote extensive bone growth. After the 4 week implantation period, Bonelike® resorption was recognized, which may be due to the presence of resorbable β and α-tricalcium phosphate phases.
Conference code: 63332Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Oliveira, J.M.; Inst. de Engenharia Biomédica, Lab. de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jmolive@fe.up.ptReferences: Praemer, A., Furner, S., Rice, D.P., (1992) Am. Acad. Orthop. Surg., p. 1;Glowacki, J., Mulliken, J.B., (1985) Clin. Plast. Surg., 12, p. 233; Buck, B.E., Malinin, T.I., Brown, M.D., (1989) Clin. Orthop., 36, p. 129; Sepulveda, P., Bressiani, A.H., Bressiani, J.C., Mesenguer, L., König Jr., B., (2002) J. Biomed. Mater. Res. Vol., 62, p. 587; Glimcher, M.J., (1987) Instr. Course Lect., 36, p. 46; Yakamuro, T., Hench, L.L., Wilson, J., (1990) CRC Handbook of Bioactive Ceramics, 2, pp. 245-252; Klemm, K.W., (1993) Clin. Orthop. & Rel. Res., 295, pp. 63-76; Agrawal, C.M., Ray, R.B., (2001) J. Biomed. Mater. Res., 55, p. 141; Santos, J.D., Campbell, J.K., Winton, G.H., (2000), European Patent N° W00068164Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463
Keywords: Bacteria; Biodegradation; Bone; Bonelike resorption; Bonelike®; Histological studies; histology; Hybrid materials; hydroxyapatite; In vivo; physiology; PLGA; Polymers; Surgery; Tissue

Bounds for the Average Generalization Error of the Mixture of Experts Neural Network - Alexandre, L.A.; Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
In this paper we derive an upper bound for the average-case generalization error of the mixture of experts modular neural network, based on an average-case generalization error bound for an isolated neural network. By doing this we also generalize a previous bound for this architecture that was restricted to special problems. We also present a correction factor for the original average generalization error, that was empirically obtained, that yields more accurate error bounds for the 6 data sets used in the experiments. These experiments illustrate the validity of the derived error bound for the mixture of experts modular neural network and show how it can be used in practice. © Springer-Verlag 2004.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; Networks and Multimedia Group, IT, Covilhã, Portugal; email: lfbaa@di.ubi.ptReferences: Gu, H., Takahashi, H., Towards more practical average bounds on supervised learning (1996) IEEE Trans. Neural Networks, 7, pp. 953-968;Vapnik, V., (1999) The Nature of Statistical Learning Theory., , Springer; Haykin, S., (1999) Neural Networks: A Comprehensive Foundation, 2nd Edition., , Prentice Hall; Alexandre, L., Campilho, A., Kamel, M., Average error bound for the mixture of experts MNN architecture (2002) Proceedings of the 12th Portuguese Conference on Pattern Recognition, , Aveiro, Portugal; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, pp. 79-87; Auda, G., Kamel, M., Modular neural network classifiers: A comparative study (1998) J. Intel. Robotic Systems, pp. 117-129; Jordan, M., Jacobs, R., Hierarchical mixture of experts and the em algorithm (1994) Neural Computation, pp. 181-214; Jacobs, R., Peng, F., Tanner, M., A bayesian approach to model selection in hierarchical mixtures-of-experts architectures (1997) Neural Networks, 10, pp. 231-241; De Marques Sa, J., Pattern Recognition: Concepts (2001) Methods and Applications, , Springer; Blake, C., Keogh, E., Merz, C., (1998) UCI repository of machine learning databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Gu, H., Takahashi, H., Estimating learning curves of concept learning (1997) Neural Networks, 10, pp. 1089-1102; Bishop, C., (1995) Neural Networks for Pattern Recognition., , Oxford University Press; Riedmiller, M., Braun, H., A direct adaptive method for faster backpropagation learning: The RPROP algorithm (1993) IEEE International Conference on Neural Networks, pp. 586-591. , San Francisco
Keywords: Generalization error bounds; Mixture of experts; Modular neural networks

Calcium phosphate-alginate microspheres as enzyme delivery matrices - Ribeiro, C.C.; Barrias, C.C.; Barbosa, M.A. (BiomaterialsBiomaterials, 2004)
The present study concerns the preparation and initial characterisation of novel calcium titanium phosphate-alginate (CTP-alginate) and hydroxyapatite-alginate (HAp-alginate) microspheres, which are intended to be used as enzyme delivery matrices and bone regeneration templates. Microspheres were prepared using different concentrations of polymer solution (1% and 3%w/v) and different ceramic-to-polymer solution ratios (0.1, 0.2 and 0.4w/w). Ceramic powders were characterised using X-ray diffraction, laser granulometry, Brunauer, Emmel and Teller (BET) method for the determination of surface area, zeta potential and Fourier transform infrared spectroscopy (FT-IR). Alginate was characterised using high performance size exclusion chromatography. The methodology followed in this investigation enabled the preparation of homogeneous microspheres with a uniform size. Studies on the immobilisation and release of the therapeutic enzyme glucocerebrosidase, employed in the treatment of Gaucher disease, were also performed. The enzyme was incorporated into the ceramic-alginate matrix before gel formation in two different ways: pre-adsorbed onto the ceramic particles or dispersed in the polymeric matrix. The two strategies resulted in distinct release profiles. Slow release was obtained after adsorption of the enzyme to the ceramic powders, prior to preparation of the microspheres. An initial fast release was achieved when the enzyme and the ceramic particles were dispersed in the alginate solution before producing the microspheres. The latter profile is very similar to that of alginate microspheres. The different patterns of enzyme release increase the range of possible applications of the system investigated in this work. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 92Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2003.11.028PubMed ID: 15046927Language of Original Document: EnglishCorrespondence Address: Ribeiro, C.C.; Laboratório de Biomateriais, INEB, Inst. de Engenharia Biomédica, Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: cribeiro@ineb.up.ptChemicals/CAS: Alginates; alginic acid, 9005-32-7; calcium phosphate, 10103-46-5; Calcium Phosphates; Drug Carriers; Enzymes, Immobilized; Glucosylceramidase, EC 3.2.1.45; Glucuronic Acid, 576-37-4; Hexuronic Acids; PowdersReferences: Griffith, L.G., Naughton, G., Tissue engineering: Current challenges and expanding opportunities (2002) Science, 295, pp. 1009-1014;Hench, L.L., Polak, J.M., Third-generation biomedical materials (2002) Science, 295, pp. 1014-1017; Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomaterials, 21, pp. 2405-2412; Laurencin, C.T., Lu, H.H., Polymer-ceramic composites for bone tissue engineering (2000) Bone Engineering, pp. 463-472. , J.E. Davies. Toronto, Canada: EM Squared Inc; Gauthier, O., Bouler -., J.M., Weiss, P., Bosco, J., Daculsi, G., Aguado, E., Kinetic study of bone ingrowth and ceramic resorption associated with the implantation of different injectable calcium-phosphate bone substitutes (1999) J Biomed Mater Res, 47, pp. 28-35; Dupraz, A., Delecrin, J., Moreau, A., Pilet, P., Passut, N., Long term bone response to particulate injectable ceramic (1998) J Biomed Mater Res, 42, pp. 368-375; Grimandi, G., Weiss, P., Millot, F., Daculsi, G., In vitro evaluation of a new injectable calcium phosphate material (1998) J Biomed Mater Res, 39, pp. 660-666; Gauthier, O., Boix, D., Grimandi, G., Aguado, E., Bouler, J.M., Weiss, P., Daculsi, G., A new injectable phosphate biomaterial for immediate bone filling of extraction sockets: A preliminary study in dogs (1999) J Periodontol, 70, pp. 375-383; Peter, S.J., Nolley, J.A., Widmer, M.S., Mervin, J.E., Yaszemski, M.J., Yasko, A.W., Engel, P.S., Mikos, A.G., In vitro degradation of a poly (propylene fumarate)/β-tricalcium phosphate composite orthopedic scaffold (1997) Tissue Eng, 3, pp. 207-215; Sims, C.D., Butler, P.E.M., Casanova, R., Lee, B.T., Randolph, M.A., Lee, W.P.A., Vacant, C.A., Yamremchuk, M.J., Injectable cartilage using polyethylene oxide polymer substrates (1996) Plast Reconstr Surg, 98, pp. 843-850; Suggs, L.J., Shive, M.S., Garcia, C.A., Anderson, J.M., Mikos, A.G., In vitro cytotoxicity and in vivo biocompalibility of poly (propylene fumarate-co-ethylene glycol) hydrogels (1999) J Biomed Mater Res, 46, pp. 22-32; Suggs, L.J., Krishnan, R.S., Garcia, C.A., Peter, S.J., Anderson, J.M., Mikos, A.G., In vitro and in vivo degradation of poly(propylene fumarate-co-ethylene glycol) hydrogels (1998) J Biomed Mater Res, 42, pp. 312-320; Frazier, D.D., Lathi, V.K., Gerhart, T.N., Hayes, W.C., Ex vivo degradation of a poly (propylene glycol-fumarate) biodegradable particulate bone cement (1997) J Biomed Mater Res, 35, pp. 383-389; Kharas, G.B., Kamanetsky, M., Simantirakis, J., Beinlich, K.C., Rizzo, A.-.M.T., Caywood, G.A., Watson, K., Synthesis and characterization of fumarate-based polyesters for use in bioresorbable bone cement composites (1997) J Appl Polym Sci, 66, pp. 1123-1137; Paige, K.T., Cima, L.G., Yaremchuck, M.J., Vacant, J.P., Vacant, C.A., Injectable cartilage (1995) Plast Reconstr Surg, 96, pp. 1390-1400; Paige, K.T., Cima, L.G., Yaremchuck, M.J., Vacant, J.P., Vacant, C.A., De novo cartilage generation using calcium-alginate-chondrocyte constructs (1996) Plast Reconstr Surg, 97, pp. 168-180; Kulseng, B., Skjak-Braek, G., Ryan, L., Andersson, A., King, A., Faxvaag, A., Espevik, T., Transplantation of alginate microcapsules (1999) Transplantation, 67, pp. 978-984; Martinetti, R., Dolcini, L., Ravaglioli, A., Krajewski, A., Mangano, C., Experimental study on hydroxyapatite/N-carboxymethyl chitosan fillers (1997) Bioceramics, 10, pp. 503-506. , L. Sedel, & C. Rey. Oxford, UK: Elsevier; Maruyama, M., Ito, M., In vitro properties of a chitosan-bonded self hardening paste with hydroxyapatite granules (1996) J Biomed Mater Res, 32, pp. 527-532; Dupraz, A., Nguyen, T.P., Richard, M., Daculsi, G., Passuti, N., Influence of a cellulosic ether carrier on the structure of biphasic calcium phosphate ceramic particles in an injectable composite material (1999) Biomaterials, 20, pp. 663-673; Ribeiro, C.C., Ma, B., Calcium-Titanium-Phosphate: A Potential Material to Be Used in the Biomedical Field, , submitted for publication; Alamo, J., Chemistry and properties of solids with NZP skeleton (1993) Solid State Ionics, 63, pp. 547-561; Takahiro, S., Motohiro, T., Hosono, H., Application of a microporous glass-ceramic with a skeleton of CaTi 4(PO 4) 6 to carriers for immobilization of enzymes (1991) J Ferment Bioeng, 72, pp. 384-391; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue response in femur of rabbits after implantation of a new calcium titanium phosphate composition (2001) Key Eng Mater, 192-195, pp. 383-386; Otsuka, M., Matsuda, Y., Fox, J.L., Higuchi, W.I., Yu, D., Wong, J., A novel skeletal drug delivery system for anti bacterial drugs using self-setting hydroxyapatite cement (1990) Chem Pharm Bull (Tokyo), 38, pp. 3500-3502; Guicheux, J., Grimandi, G., Trecant, M., Faivre, A., Takahashi, S., Apatite as a carrier for growth hormone: In vitro characterization of loading and release (1997) J Biomed Mater Res, 34, pp. 165-170; Gombotz, W.R., Wee, S.F., Protein release from alginate matrices (1998) Adv Drug Deliv Rev, 31, pp. 267-285; Eiselt, P., Yeh, J., Latvala, R.K., Shea, L.D., Mooney, D.J., Porous carriers for biomedical applications based on alginate hydrogels (2000) Biomaterials, 21, pp. 1921-1927; Alsberg, V., Anderson, K., Albeiruti, A., Franceshi, R.T., Mooney, D.J., Cell interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Smidsrod, O., Draget, K.I., Chemistry and physical properties of alginates (1996) Carbohyd Europe, 14, pp. 6-13; Sivakumar, M., Manjubala, I., Panduranga Rao, K., Preparation, characterization and in-vitro release of gentamicin from coralline hydroxyapatite-chitosan composite microspheres (2002) Carbohyd Pol, 49, pp. 281-288; Qiu, Q.Q., Ducheyne, P., Ayyaswamy, P.S., New bioactive, degradable composite microspheres as tissue engineering substrates (2000) J Biomed Mater Res, 52, pp. 66-76; Hsu, F.Y., Chueh -., S.C., Wang, Y.J., Microspheres of hydroxyapatite/reconstituted collagen as supports for osteoblast cell growth (1999) Biomaterials, 20, pp. 1931-1936; Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev, 12, pp. 115-133; Xu, Y.H., Ponce, E., Sun, Y., Leonova, T., Bove, K., Witte, D., Grabowski, G.A., Turnover and distribution of intravenously administered mannose-terminated human acid beta glucosidase in murine and human tissues (1996) Pediatr Res, 39, pp. 313-322; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., Effect of chemical composition on hydrophobicity and zeta-potential of plasma spayed HA/CaO-P 2O 5 glass coatings (2001) Biomaterials, 22, pp. 3105-3112; Lopes, M.A., Monteiro, F.L., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Dupuy, B., Arien, A., Minnot, A.P., FT-IR membranes made with alginate/polylysine complexes. Variations with mannuronic or guluronic content of the polysaccharides. Art Cells, Blood Subs (1994) Immob Biotech, 20, pp. 71-82; Peters, T., (1996) All about Albumin: Biochemistry, Genetics and Medical Applications, , San Diego, CA: Academic Press Inc; Nakanishi, K., Sakiyama, T., Imamura, K., On the adsorption of proteins on solid surfaces, a common but very complicated phenomenon (2001) J Biosci Bioeng, 91, pp. 233-244
Keywords: Absorption; Adsorption; Alginate; Alginates; article; Biomaterials; Bone; Calcium Compounds; Calcium phosphates; Calcium titanium phosphate; calcium titanium phosphate alginate; ceramics; Drug Carriers; Drug Delivery Systems; Enzyme delivery; Enzyme-delivery; Enzymes; Enzymes, Immobilized; Fourier transform infrared spectroscopy; Glucosylceramidase; Glucuronic Acid; Hexuronic Acids; High performance liquid chromatography; hydroxyapatite; hydroxyapatite alginate; laser; methodology; microsphere; Microspheres; Molecular Conformation; Particle Size; Powders; priority journal; surface property; unclassified drug; X ray diffraction

CaO-P 2O 5 Glass-Hydroxyapatite Thin Films Obtained by Laser Ablation: Characterisation and In Vitro Bioactivity Evaluation - Ferraz, M.P.; Monteiro, F.J.; Gião, D.; Leon, B.; Gonzalez, P.; Liste, S.; Serra, J.; Arias, J.; Perez-Amor, M. (Key Engineering MaterialsKey Eng Mat, 2004)
Hydroxyapatite (HA) coatings have been applied to improve adhesion of non-cemented implants to host bone. Plasma spraying is the most common technique leading to thick calcium phosphate films (>120μm). Pulse laser deposition (PLD), is a possible alternative method to obtain thin (<10 μm), well adherent hydroxyapatite (HA) films. Similarly to synthetic HA, biological apatites contain Ca 2+, PO 4 3- and OH
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: mpferraz@ufp.ptReferences: Arias, J.L., (1997) J Mater. Sci. Mater. Med., 8, pp. 873-876;Peraire, C., (1997) 13 th European Conference on Biomaterials, p. 75. , Göteborg, Sweden, 4-7 Sept; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J Biomed Mater Res, 45, p. 373; Ferraz, M.P., Fernandes, M.H., Trigo-Cabral, A., Santos, J.D., Monteiro, F.J., (1999) J. Mat Sci: Mat. Med, 10 (9), p. 567
Keywords: 2O; 5 glass; Adhesion; Bioactivity; Bone; Calcium Compounds; CaO-P; Coatings; Deposition; Energy dispersive spectroscopy; Homogeneous mixtures; Hydroxylapatite thin films; Implants (surgical); In vitro bioactivity; Laser ablation; Plasma spraying; Scanning electron microscopy; Thin films; X ray diffraction

Combining Foaming and Starch Consolidation Methods to Develop Macroporous Hydroxyapatite Implants - Lemos, A.F.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2004)
Hydroxyapatite (HA) is the calcium-phosphate material with composition closest to that of bone, what makes it suitable for osseous implant purposes. This material was used to produce macroporous structures with pores larger than 100 μm, which are believed to be suitable for allowing bone ingrowth. The macroporous structures were generated and consolidated by combining foaming and starch consolidation methods. The porous structures could be tailored according to the final application by varying the proportion of different foaming agents, foam-bath concentrate (FBC) and sodium lauril sulphate (SLS). Playing with these proportions it was also possible to improve foam stability and model the size of pores and pore interconnections in order to reproduce the pore structure of natural bone.
Conference code: 62053Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Lemos, A.F.; Depto. de Engenharia Cerâmica, CICEO, Campus de Santiago, 3810-193 Aveiro, Portugal; email: ilemos@cv.ua.ptReferences: De Groot, K., (1983) Bioceramics of Calcium Phosphates, , CRC Press, Boca Raton, FL;Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, , World Scientific, London, UK; Ohgushi, H., Okumura, M., Yoshikawa, T., Inoue, K., Senpuku, N., Tamai, S., Shors, E.C., (1992) J. Biomed. Mater. Res., 26, p. 885; Minnear, W.P., (1992) Processing of Foamed Ceramics, Ceramic Transactions, Forming Science and Technology for Ceramics Vol. 26, 26. , ed. M.J. Cima, The American Ceramic Society, USA; Omatete, O., Janney, M.A., Strehlow, R.A., (1991) Am. Ceram Soc.Bull., 70, p. 1641; Kosmac, T., Novak, S., Sajko, M., (1995) Fourth Euro Ceramics, Vol. 1, Basic Science Developments, 1. , ed. C. Galassi. Gruppo Editoriale Faenza Editrice S.p.a., Italy; Graule, T.J., Baader, F.H., Gauckler, L.J., (1994) Cfi/Ber. DKH., 71, p. 317; Novich, B.E., Sundback, C.A., Adams, R.W., (1992) Ceramic Transactions, 26. , ed. M. J. Cima. American Ceramic Society, USA; Rives, R.D., U. S. Patent 4113480 (1976)Lycfeldt, O., Brandt, J., Lesca, S., (2000) J. Eur. Ceram. Soc., 20 (14-15), p. 2551; Olhero, S.M., Tarì, G., Coimbra, M.A., Ferreira, J.M.F., (2000) J. Eur. Ceram. Soc., 20 (4), p. 423; Lycfeldt, O., Ferreira, J.M.F., (1998) J. Eur. Ceram. Soc., 18, p. 131; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., (2003) Advanced Materials Forum, , in press
Keywords: Bioceramics; Biocompatibility; Bone; Composition; Foaming method; hydroxyapatite; Hydroxyapatlte; Implants (surgical); Macroporous structures; Microstructure; Pore size; Porous ceramics; Porous materials; Starch; Starch consolidation

A comparative study of CaO-P 2O 5-SiO 2 gels prepared by a sol-gel method - Hussain, N.S.; Lopes, M.A.; Santos, J.D. (Materials Chemistry and PhysicsMater Chem Phys, 2004)
This paper reports on the results concerning the preparation and systematic analysis of CaO-P 2O 5-SiO 2 gels by a sol-gel process. The concentration of SiO 2 influence on these gels and found the results are very encouraging. Studies have revealed that the concentration of SiO 2 has a marginal influence on the phase formation of these gels. It has appreciable changes from less configured particles at lower values of concentration, with an ultimate growth in a highly crystalline fibrous nature at higher concentrations of SiO 2. The authors have examined the changes in the morphology of these gels by a scanning electron microscope with an energy dispersive analyser (SEM/EDS techniques) and also from the profiles of Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) spectral data and reported the crystalline product containing the fibrous β-Ca(PO 3) 2 as a major phase in the materials studied. © 2004 Elsevier B.V. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: MCHPDdoi: 10.1016/j.matchemphys.2004.06.015Language of Original Document: EnglishCorrespondence Address: Hussain, N.S.; DEMM, Faculty of Engineering, University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: sooraj@fe.up.ptReferences: Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487;Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, , World Scientific, Singapore; Ohtsuki, C., Kokubo, T., Yamamuro, T., (1992) J. Non-cryst. Solids, 143, p. 84; Kokubo, T., Yoshihara, S., Nishimura, N., Yamamuro, T., Nakamura, T., (1991) J. Am. Ceram. Soc., 74, p. 1739; Ota, Y., Iwashita, T., Kasuga, T., Abe, Y., Seki, A., (2001) Key Eng. Mater., 192-195, p. 421; Kasuga, T., Ota, Y., Nogami, M., Abe, Y., (1996) Phos. Res. Bull., 6, p. 75; Ota, Y., Kasuga, T., Abe, Y., (1997) J. Am. Ceram. Soc., 80 (1), p. 225; Zhang, Y., Santos, J.D., (2000) J. Non-cryst. Solids, 227, p. 14; Yoldas, B.E., (1975) Ceram. Bull., 54, p. 286; Thomas, I.M., (1988) Sol-gel Technology for Thin Films, Fibres, Preforms, Electronics and Specialty Shapes, p. 2. , L.C. Klein (Ed.), Noyes, NJ; Brinker, C.J., Scherer, G.W., (1990) Sol-gel Science: The Physics and Chemistry of Sol-gel Processing, , Academic Press, New York; Hench, L.L., West, J.K., (1990) Chem. Rev., 90, p. 33; Hench, L.L., (1998) Sol-gel Silica: Properties, Processing and Technology Transfer, , Noyes, New Jersey; Salinas, A.J., Martin, A.I., Vallet-Regí, M., (2002) J. Biomed. Mater. Res., 61 (4), p. 524; Laczka, M., Cholewa, K., Lazca-Osyczka, A., (1997) J. Alloys Comp., 248, p. 42; Roman, J., Padilla, S., Vallet-Regí, M., (2003) Chem. Mater., 15 (3), p. 798; Li, R., Clark, A.E., Hench, L.L., (1991) J. Appl. Biomater., 2, p. 231; Rámila, A., Vallet-Regí, M., (2001) Biomaterials, 22, p. 2301; Balas, F., Arcos, D., Pérez-Pariente, J., Vallet-Regí, M., (2001) J. Mater. Res., 16 (5), p. 1345; Peitl, O., Zanotto, E.D., Hench, L.L., (2001) J. Non-cryst. Solids, 292, p. 115; Casu, M., Casula, M.F., Corrias, A., Pachina, G., (2003) J. Non-cryst. Solids, 315, p. 97; Motke, S.G., Yawale, S.P., Yawale, S.S., (2002) Bull. Mater. Sci., 25 (1), p. 75; Méndez-Vivar, J., Mendoza-Bandala, A., (2000) J. Non-cryst. Solids, 261, p. 127; Popa, M., Calderon-Moreno, J.M., Popescu, L., Kakihana, M., Torecillas, R., (2002) J. Non-cryst. Solids, 297, p. 290; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2002) Spectrosc. Lett., 35 (2), p. 275; Mackenzie, J.D., (1986) Science of Ceramic Chemical Processing, p. 112. , L.L. Hench, D.R. Ulrich (Eds.), Wiley/Interscience; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Jpn. Assoc. Apatite Sci. (JASS)
Keywords: Bioactivity; Calcium Compounds; Calcium phosphosilicates; Fourier transform infrared spectroscopy; Gels; morphology; Phase composition; Phase formation; Phosphorus Compounds; Scanning electron microscopy; Silica; Sol-gel process; Sol-gels; X ray diffraction analysis

Crystallisation studies of biodegradable CaO-P 2O 5 glass with MgO and TiO 2 for bone regeneration applications - Dias, A.G.; Tsuru, K.; Hayakawa, S.; Lopes, M.A.; Santos, J.D.; Osaka, A. (Glass TechnologyGlass Technol, 2004)
CaO-P 2O 5 glass ceramics with small additions of MgO and TiO 2 were prepared in the ortho and pyrophosphate regions by powder sintering and crystallisation through heat treatment at different temperatures determined from differential thermal analysis (DTA). The glass ceramics were analysed by x-ray diffraction (XRD) and it was observed that α- and β-Ca 2P 2O 7 were the first phases to precipitate in the parent glass matrix at a temperature of 681°C, followed by CaTi 4(PO 4) 6 and TiP 2O 7 at temperatures between 703 and 725°C. The β-Ca 2P 2O 7 and CaTi 4(PO 4) 6 phases are usually considered as biocompatible and bioactive and, therefore, these glass ceramics seem to show good potential for bone regeneration applications.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: GLSTALanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB, Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Siligardi, C., D'Arrigo, M.C., Leonelli, C., Sintering behavior of glass ceramics frits (2000) Am. Ceram. Soc. Bull., pp. 88-92;Clarck, T.J., Reed, J.S., Kinetic processes involved in the sintering and crystallization of glass powders (1986) J. Am. Ceram. Soc., 69 (11), pp. 837-846; Karmakar, B., Kundu, P., Jana, S., Dwivedi, R.N., Crystallization kinetics and mechanism of low-expansion lithium aluminosilicate glass-ceramics by dilatometry (2002) J. Am. Ceram. Soc., 85 (10), pp. 2572-2577; Zhang, Y., Santos, J.D., Crystallization and microstructure analysis of calcium phosphate-based glass ceramics for biomedical applications (2000) J. Non-cryst. Solids, 272 (1), pp. 14-21; Ryu, H.-S., Youn, H.-J., Chang, B.-S., Lee, C.-K., Chung, S.-S., An improvement in sintering property of β-tricalcium phosphate by addition of calcium pyrophosphate (2002) Biomaterials, 23, pp. 909-914; Kitsugi, T., Yamamuro, T., Nakamura, T., Ota, M., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorous molar ratios (1995) Biomaterials, 16, pp. 1101-1107
Keywords: Biodegradation; Bone Regeneration; Crystallization; Differential thermal analysis; Diffractometers; Glass ceramics; Glass matrix; Glass transition; Laser diffraction; Lime; Magnesia; methanol; Monochromators; Precipitation (chemical); Temperature scanning; Titanium dioxide; X ray powder diffraction

Designing of Bioceramics with Bonelike Structures Tailored for Different Orthopaedic Applications - Lemos, A.F.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2004)
Innovative methods for the production of porous bioceramics for implants with tailored pore volume fractions, pore sizes, pore size distributions and pore interconnectivity have been developed. The average pore sizes can vary from a few micrometers to more than one millimeter, therefore fulfilling all the needs required for components used in implantology. The methods combine in a suitable way the knowledge coming from different areas in the field of colloid and interface science, namely, on the processing of ceramic materials by traditional colloidal shaping techniques such as slip casting with a number of new direct consolidation techniques, which transform the fluid hydroxyapatite (HA) based suspensions into rigid bodies, and particularly the expertise in the production of porous ceramics by different techniques. Slip casting was preferably used for designing the cortical part of the bone, while direct consolidation techniques were used to "freeze" tailored foamy structures or suspensions containing different kinds of organic inclusions of suitable sizes and amounts that generate pores after burning out.
Conference code: 62053Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Lemos, A.F.; Depto. de Engenharia Cerâmica, CICECO, Campus de Santiago, 3810-193 Aveiro, Portugal; email: ilemos@cv.ua.ptReferences: Hing, K.A., Best, S.M., Tanner, K.E., Bondfield, W., Revell, P.A., (1997) J. Mater. Sci: Mater Med., 8, p. 731;Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Kon, E., Muraglia, A., Corsi, A., Bianco, P., Marcacci, M., Martin, I., Boyde, A., Quarto, R., (2000) J. Biomed. Mater. Res., 49 (3), p. 328; Prado da Silva, M.H., Lemos, A.F., Lopes, M.A., Ferreira, J.M.F., Santos, J.D., (2002) Journal of Non-crystalline Solids, 304, p. 286; Schwartzwalder, K., Somers, A.V., U.S. Patent n° 3 090 094, (1963)Saggio-Woyanski, J., Scott, C.E., Minnear, W.P., (1992) Amer. Ceram. Soc. Bull., 71 (11), p. 1674; Olhero, S.M., Tarì, G., Coimbra, M.A., Ferreira, J.M.F., (2000) J. Eur. Ceram. Soc., 20 (4), p. 423; Lyckfeldt, O., Ferreira, J.M.F., (1998) J. Eur. Ceram. Soc., 18, p. 131; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., (2003) Advanced Materials Forum, , in press; Lyckfeldt, O., Brandt, J., Lesca, S., (2000) J. Eur. Ceram. Soc., 20 (14-15), p. 2551
Keywords: Bioceramics; Biocompatibility; Bone; Cells; Ceramic materials; Consolidation techniques; hydroxyapatite; morphology; orthopedics; Pore size; Porous ceramics; Porous materials; Sintering; Slip casting

Detection of Rib Borders on X-ray Chest Radiographs - Moreira, R.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
The purpose of the research herein presented is the automatic detection of the rib borders in posterior-anterior (PA) digital chest radiographs. In a computer-aided diagnosis system, the precise location of the ribs is important as it allows reducing the false positive in the detection of abnormalities such as nodules, rib lesions and lung lesions. We adopted an edge based approach aiming at detecting the lower border of each rib. For this purpose, the rib geometric model is described as a parabola. For each rib, the upper limit is obtained using the position of the corresponding lower border. © Springer-Verlag 2004.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: INEB - Instituto de Engenharia Biomedica, Laboratóries de Sinai, Imagem BiomédicaPortugalReferences: Volgelsang, F., Weiler, F., Dahmen, J., Kilbinger, M., Wein, B., Günther, R.W., (1998) Detection and Compensation of Rib Structures in Chest Radiographs for Diagnose Assistance, Proceedings of SPIE, 3338, pp. 774-785;Park, M., Jin, J.S., Wilson, L.S., Detection and labeling ribs on expiration chest radiographs (2003) The Phisics of Medical Imaging Conference, SPIE, pp. 1021-1031. , 15-20 Feb; Ginneken, B., Romeny, Bart, M.H., Automatic delineation of ribs in frontal chest radiographs (2000) Medical Imaging 2000:Image Processing, Proceedings of SPIE, 3979, pp. 825-836; Monteiro, M., Mendonça, A.M., Campilho, A., Lung field detection on chest radiographs (2002) Proceedings of VIIP02, pp. 367-372. , IASTED International Conference on Visualization, Imaging and Image Processing, Spain; Mendonça, A.M., Suva, J., Campilho, A., Automatic delimitation of lung fields on chest radiographs (2004) Proceeding of ISBI04, IEEE International Symposium on Biomedical Imaging, , Arlington, USA; Otsu, N., A threshold selection method from gray-level histograms (1979) IEEE Transactions on Systems, Man, and Cybernetics, 9 (1), pp. 62-66

Effect of the Solvents on the Solution Mixture Derived Polylactide/hydroxyapatite Composites - Li, Y.; Weng, W.; Cheng, K.; Du, P.; Shen, G.; Han, G.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2004)
Polylactide/hydroxyapatite composites were prepared by a solution mixture method. Chloroform and tetrahydrofuran were used as solvents. The effect of the solvents on the polylactide/hydroxyapatite composites was investigated by TEM, mechanical properties, sedimentation time and UV-Vis transmission spectra. The results indicate that the polylactide/hydroxyapatite prepared using tetrahydrofuran as solvent has better dispersion of the hydroxyapatite filler in the matrix and larger bend strength than the one using chloroform as solvent. This is ascribed to the proper interaction between the solvent and hydroxyapatite filler.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Weng, W.; Dept. of Mat. Sci. and Engineering, Zhejiang University, Hangzhou 310027, China; email: wengwj@zju.edu.cnReferences: Hench, L.L., (1998) Journal of American Ceramic Society, 81, p. 1705;Wang, M., (2003) Biomaterials, 24, p. 2133; Hao, J., Yuan, M., Deng, X., (2001) Biomaterials, 22, p. 2867; Ignjatovic, N., Tomic, S., Dakic, M., Miljkovic, M., Plavsic, M., Uskokovic, D., (1999) Biomaterials, 20, p. 809; Misra, D.N., (1988) Langmuir, 4, p. 953; Dean, J.A., (1999) Lange's Handbook of Chemistry (15th Edition), , McGraw-HILL, INC. New York
Keywords: Bend strength; Composite; Composite materials; dispersion; Dispersions; Fillers; Heat treatment; Hydroxvapatite; hydroxyapatite; Polarity; polylactide; Sedimentation; Solutions; Solvent; Solvents; transmission electron microscopy; Ultraviolet radiation

Effects of some variables on R.F. Magnetron Sputtered Hydroxyapatite Coatings on Titanium - Silva, R.A.; Sousa, M.; Monteiro, F.J.; Barral, R.; Santos, J.D.; Lopes, M.A. (Key Engineering MaterialsKey Eng Mat, 2004)
RF sputtering may be used to produce thin, well adherent bioactive coatings with long term stability to ensure contact with bone tissue. RF Sputtered Hydroxyapatite (HA) coatings were produced onto Ti at 200 and 150 W. S.E.M. analysis indicated that films obtained with 200 W were thicker than those with 150 W. Significant variations were observed, depending on the location of the substrates with respect to the sample holder in the sputtering chamber, with thickness ranging from 1.8 to 3.2 μm. EDS analysis of 200 W films revealed the presence of Ca and P, in ratios typical of HA. XPS of thinner films obtained at 150 W, showed Ca and P, but also some carbonate probably partially substituting OH. Anodic polarisation curves of samples coated at 200 W and 150 W and for different sputtering times, compared to Ti substrate, indicate that HA films were protective and that the degree of protection increased with film thickness, i.e., with power intensity and time of deposition.
Conference code: 62053Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Silva, R.A.; Inst. Sup. de Engenharia do Porto, Rua Dr. Antonio Bernardino A., 431, 4200-072 Porto, Portugal; email: ras@isep.ipp.ptReferences: Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., (1997) Journal of Materials Science: Materials in Medicine, 8, pp. 731-736;Raynaud, S., Champion, E., Bernache-Assolant, D., Tetard, D., (1998) Journal of Materials Science: Materials in Medicine, 9, pp. 221-227; Weng, J., Liu, X., Zhang, X., De Groot, K., (1996) Journal of Biomedical Materials Research, 30, pp. 5-11; Gross, K.A., Gross, V., Berndt, C.C., (1998) Journal of the American Ceramic Society, 81 (1), pp. 106-112; Edwards, J.T., Brunski, J.B., Higuchi, (1997) Journal of Biomedical Materials Research, 36, pp. 454-468; Yang, C.Y., Lin, R.M., Wang, B.C., Lee, T.M., Chang, E., Hang, Y.S., Chen, P.Q., (1997) Journal of Biomedical Materials Research, 37, pp. 335-345; Ogiso, M., Yamamura, M., Kuo, P.T., Borgese, D., Matsumoto, T., (1998) Journal of Biomedical Materials Research, 39, pp. 364-372; Van Dijk, K., Schaeken, H.G., Wolke, J.G.C., Maree, C.H.M., Habraken, F.H.P.M., Jansen, J.A., (1995) Materials in Clinical Applications, pp. 249-256. , P. Vincenzini, (ed.); Yoshinari, M., Hayakawa, T., Wolke, J.G.C., Nemoto, K., Jansen, J.A., (1997) Journal of Biomedical Materials Research, 37, pp. 60-67; Wolke, J.G.C., De Groot, K., Jansen, J.A., (1998) Journal of Biomedical Materials Research, 39, pp. 524-530
Keywords: Bioactive coatings; Bone; Coatings; Corrosion protection; hydroxyapatite; Magnetron sputtering; Plasma spraying; Polarization; RF sputtering; Scanning electron microscopy; Sputter deposition; Sputtering chambers; Thin films; Titanium

Electrochemical behaviour of titanium coated stainless steel by r.f. sputtering in synthetic sweat solutions for electrode applications - Fonseca, C.; Vaz, F.; Barbosa, M.A. (Corrosion ScienceCorros. Sci., 2004)
The r.f. sputtering technique was used to deposit titanium thin films on stainless steel substrates, aiming at the application of the coated samples as skin contact materials for "dry" active electrodes. In this work the electrochemical behaviour of the coated samples was investigated in synthetic sweat solutions and their performance was compared with that of uncoated stainless steel and bulk titanium. The characterisation of the samples was carried out by electrochemical techniques and scanning electron microscopy. The coated samples displayed corrosion resistance values in synthetic sweat solutions much higher than stainless steel samples and of the same order of the values measured for bulk titanium in the same conditions. © 2004 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: CRRSAdoi: 10.1016/j.corsci.2004.04.006Language of Original Document: EnglishCorrespondence Address: Fonseca, C.; Inst. de Engenharia Biomédica, Laboratorio de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cfonseca@fe.up.ptReferences: Cooper, R., Osselton, J.W., Shaw, J.C., (1980) EEG Technology, pp. 20-28. , Butterworths and Co. Ltd;Femandez, M., Pallas-Aieny, R., (2000) Biomed. Iustrum. Technol., pp. 125-130. , March/April; Searle, A., Kirkup, L., (2000) Physiol. Meas., 21, pp. 271-283; Mancuso, G., Tosti, A., Fanti, P.A., Berdondini, R.M., Mongiorgi, R., Morandi, A., (1990) Dermatologica, 181, pp. 324-326; Puig, L., Rocamora, V., Romani, J., Saavedra, M., Alomar, A., (1989) Pediatr. Dermatol., 15, pp. 27-30; Ko, W.K., Hynecek, J., Dry electrodes and electrode amplifiers (1974) Biomedical Electrode Technology, , HA. Miller, D.C. Harrison (Eds.), Academic Press, New York; Binnie, C.D., Rowan, A.J., Gutter, Th., (1982) A Manual of Electroencephalographic Technology, pp. 81-97. , Cambridge University Press; Tahfiri, B.A., Knight, R.T., Smith, R.L., (1998) Electroenceph. Clin. Neurophysiol., 90, pp. 376-383; Dunseath, Jr., (1991), NoB-polarizable dry biomedical electrode, US patent 5,003,978Burke, M.J., Gleeson, D.T., (2000) IEEE Trans. Biomed. Eng., 47 (2), pp. 155-162; Taheri, B., (2002), Biopotential sensor electrode, US patent 6,434,424 B1Pan, J., Leygraf, C., Ektressabi, A.M., (1997) J. Biomed. Mater. Res., 35, pp. 309-318; Fathi, M.H., Salehi, M., Saatchi, A., Mortazavi, V., Moosavi, S.B., (2003) Dent. Mater., 19, pp. 188-198; Kao, C.T., Ding, S.J., Chen, Y.C., Huang, T.H., (2002) J. Biomed. Mater. Res., 63 (6), pp. 786-792; Dogan, H., Findik, F., Morgnl, O., (2002) Mater. Des., 23 (7), pp. 605-610; Randin, J.-O., (1988) J. Bjomed. Mater. Res., 22, pp. 649-666; Aladjem, A., (1973) J. Mater. Sci., 8, pp. 688-693; Cai, Z., Nakajima, H., Woldu, M., Berglund, A., Bergman, M., Okabe, T., (1999) Biomaterials, 20, p. 183190; Caao, C.Y., Jin, L.F., Macdonald, D.D., (1982) J. Electrochem. Soc., 129, pp. 1874-1879; Armstrong, R.D., Edmondson, K., (1973) Electrochim. Acta, 18, pp. 937-943; Femandes, J., (1997) Corrosão Por Picadas Em Aluminio Modificado Por Implantaçáo Ióica De Tungsténio, , PhD thesis, IST, Lisbon; Rammelt, U., Reinhard, G., (1987) Corros. Sci., 27, pp. 373-382; Park, J.R., MacDonald, D.D., (1983) Corros. Sci., 23, pp. 295-315; MacDonald, J.R., Johnson, W.B., (1987) Impedance Spectroscopy, , John Wiley, New York
Keywords: A. Sputtered films; A. Stainless steel; A. Titanium; B. EIS; coating; Corrosion resistance; Electrochemical corrosion; Electrochemical techniques; electrochemistry; electrode; Electrodes; Protective coatings; Scanning electron microscopy; Sputtering; Stainless steel; Synthetic sweat solutions; Thin films; Titanium

An electronic instrumentation course for non-electronic engineering students - Campilho, A.; Cardoso, A. (International Journal of Electrical Engineering EducationInt J Electr Eng Educ, 2004)
This paper reports on the implementation of a required course on electronic instrumentation for informatics engineering students. These students had proved in previous years to require a special approach, as their motivation for this subject was low. The course focuses on the basic concepts of Electronic Instrumentation, including analogue-to-digital and digital-to-analogue conversion and introducing the concept of instrument control. The course was organised in a set of lectures coupled with laboratory experiments, and a small project. To foster collaborative learning all the students work on the same laboratory experiments, simultaneously, organised in groups of two. The students' feedback on the course was more positive than in previous years, although not substantially so in terms of results. We feel that a change of attitude took place effectively, and that this could be attributed to the laboratory experiments using LabVIEW.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: IJEEALanguage of Original Document: EnglishCorrespondence Address: Campilho, A.; Inst. de Engenharia Bioméd., Universidade do Porto, Porto, Portugal; email: campilho@fe.up.ptReferences: (2000) LabVIEW Graphical Programming for Instrumentation, , National Instruments, Austin, Texas, TX, Version 6.1;Consonni, D., Seabra, A.C., A modern approach to teaching basic experimental electricity and electronics (2000) IEEE Trans. Educ., 43, pp. 5-18; Goulart, T.J., Consonni, D., Automated system for measurement electrical three-phase power components (2001) IEEE Trans. Educ., 44, pp. 336-341; Edward, N.S., The role of laboratory work in engineering education: Student and staff perceptions (2002) Int. J. Elec. Engng. Educ., 39 (1), pp. 11-19; Jiménez-Leube, F.J., Almendra, A., González Sanz-Maudes, C., Networked implementation of an electrical measurement laboratory for first course engineering studies (2001) IEEE Trans. Educ., 44, pp. 377-383; Campilho, A., (2002) Instrumentação Electrónica. Métodos e Técnicas de Medição, , Edições FEUP, Porto
Keywords: Analog to digital conversion; Analogue-to-digital conversion; Collaborative learning; Collaborative learning (CL); Curricula; Data processing; Electronic instrumentation; Electronics engineering; Engineering education; LabVIEW; Learning systems; Motivation; Project management; Students

Fabrication of alternating polycation and albumin multilayer coating onto stainless steel by electrostatic layer-by-layer adsorption - Ji, J.; Tan, Q.; Fan, D.-Z.; Sun, F.-Y.; Barbosa, M.A.; Shen, J. (Colloids and Surfaces B: BiointerfacesColloids Surf. B Biointerfaces, 2004)
Multilayer films consisting of polyethylenimine (PEI) and albumin were successfully prepared on biomedical 316L stainless steel surface via electrostatic self-assembly of the PEI and albumin. The process of electrostatic self-assembly of PEI/albumin was monitored by 125I radiolabeling, electrochemical impedance spectroscopy (EIS) and atomic force microscopy (AFM). The EIS data revealed that the multilayer coating was stable in Tris-HCl (pH 7.35) buffer solution for 21 days. 125I radiolabeling experiments indicated that less than 10% albumin was eluted by PBS in 45 days. Static platelet adhesion experiments indicated that the PEI/albumin deposited on stainless steel could resist platelet adhesion effectively. Such an easy processing and shape-independent method may have good potential for surface modification of cardiovascular devices. © 2004 Elsevier B.V. All rights reserved.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: CSBBEdoi: 10.1016/j.colsurfb.2003.12.015PubMed ID: 15261073Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: iodine 125, 14158-31-7, 22822-81-7; polyethyleneimine, 74913-72-7; stainless steel, 12597-68-1; Albumins; Lipid Bilayers; Polyamines; polycations; Polyethyleneimine, 9002-98-6; Stainless Steel, 12597-68-1References: Thomann, U.I., Uggowitzer, P.J., (2000) Wear, 239, p. 48;Cheatham, J., (2001) Prog. Pediat. Cardiol., 14, p. 95; Donachie, M., (1998) Adv. Mater. Process, 154, p. 63; Bertrand, P., (2000) Macromol. Rapid Commun., 21, p. 319; Ulman, A., (1996) Chem. Rev., 96, p. 1533; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu. Rev. Mater. Sci., 26, p. 153; Laschewsky, A., (1997) Eur. Chem. Chronicle (ECC), 2, p. 13; Decher, G., (1997) Science, 277, p. 1232; Yoo, D., Seimei, S., Michael, F.R., (1998) Macromolecules, 31, p. 4309; Picart, C., Lavalle, Ph., Hubert, P., Cuisinier, F.J.G., Decher, G., Schaaf, P., Voegel, J.-C., (2001) Langmuir, 17, p. 7414; Houska, M., Brynda, E., (1997) J. Colloid Interf. Sci., 188, p. 243; Brynda, E., Houska, M., (1996) J. Colloid Interf. Sci., 183, p. 18; Lu, C.H., Luo, C.Q., Cao, W.X., (2002) Colloids Surf. B: Biointerf., 25, p. 19; Keogh, R.J., Eaton, J.W., (1994) J. Lab. Clin. Med., 124, p. 537; Munro, M.S., (1981) Trans. Am. Soc. Artif. Intern. Organs, 27, p. 499; Brynda, E., Houska, M., (2000) Protein Architecture: Interfacing Molecular Assemblies and Immobilization, pp. 251-285. , Y. Lvov, H. Moehwald (Eds.), Marcel Dekker, New York; Keogh, J.R., Velander, F.F., Eaton, W., (1992) J. Biomed. Mater. Res., 26, p. 441; Ji, J., Feng, L., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Lopez, G.P., Ratner, B.D., Tidwell, C.D., Haycox, C.L., Rapoza, R.J., Horbett, T.A., (1992) J. Biomed. Mater. Res., 26, p. 415; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of Biocompatibility Tests, 2, pp. 183-214. , D.F. Williams (Ed.), CRC Press, Harcover; Cheng, Z., Cheng, L., Dong, S., Yang, X., (2001) J. Electrochem. Soc., 148, p. 227; Lima, J., (2001) J. Biomed. Mater. Res., 55, p. 45; Iodine-125, a Guide to Radioiodination Techniques (1993) Amersham Life Sci., p. 64; Takahara, A., Jo, N.J., Kajiyama, T., (1989) J. Biomater. Sci. Polym. Ed., 1, p. 17; Haynes, C.A., Norde, W., (1994) Colloids Surf. B: Biointerf., 2, p. 517; Ladam, G., Gergely, C., Senger, B., Decher, G., Voegel, J.C., Schaaf, P., Cuisinier, F.J.G., (2000) Biomacromolecules, 1, p. 674; Ladam, G., Schaaf, P., Cuisinier, F.J.G., Decher, G., Voegel, J.C., (2001) Langmuir, 17, p. 878; Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., (2000) Macromol. Rapid Commun., 21, p. 319
Keywords: Adhesion; Adsorption; Albumin; Albumins; article; Atomic force microscopy; Cardiovascular devices; Chemical modification; Coatings; Electric Impedance; Electric Potential; Electrochemical impedance spectroscopy; electrochemistry; Electrons; Electrostatics; film coating; iodine 125; isotope labeling; Layer-by-layer; Lipid Bilayers; Microscopy, Atomic Force; Multilayers; Nonthrombogenic; pH effects; Platelet Adhesiveness; Polyamines; polycation; Polycations; Polyethyleneimine; priority journal; Proteins; Self assembly; Spectroscopy; Spectrum Analysis; Stainless steel; Surface modification; Surface Properties; surface property; Surface treatment; thrombocyte adhesion

Fabrication of alternating polycation and albumin multilayer coating by electrostatic layer-by-layer adsorption - Ji, J.; Tan, Q.; Fan, D.-Z.; Sun, Y.-F.; Barbosa, M.A.; Shen, J. (Journal of Materials ScienceJ Mater Sci, 2004)
The construction of albumin multilayers via the electrostatic self-assembly (ESA) method was explored. Based on the results, it was possible to develop a fast, easy processing and shape-independent method for nonthrombogenic coating.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: JMTSAdoi: 10.1023/B:JMSC.0000008087.71937.71Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnReferences: Bertrand, P., Jonas, A., Laschewsky, A., (2000) Macr. Rap. Comm., 21, p. 319;Ulman, A., (1996) Chem. Rev., 96, p. 1533; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu. Rev. Mater. Sci., 26, p. 153; Houska, M., Brynda, E., (1997) J. Coll. Interf. Sci., 188, p. 243; Brynda, E., Houska, M., (1996) J. Coll. Interf. Sci., 183, p. 18; Keogh, R.J., Eaton, J.W., (1994) J. Lab. Clin. Med., 124, p. 537; Keogh, J.R., Velander, F.F., Eaton, W., (1992) J. Biomed. Mater. Res., 26, p. 441; Ji, J., Feng, L.X., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Cheng, Z., Cheng, L., Dong, S., Yang, X., (2001) J. Electrochem. Soc., 148, pp. E227
Keywords: Adhesion; Adsorption; Albumin; Biocompatibility; Biological materials; Biopolymers; Blood; Charge transfer; Chemical bonds; Covalent binding; Desorption; Electron transfer; Electron transfer resistance; Electrostatic layer by layer adsorption; Electrostatics; Multilayers; polycation; Positive ions; Spectroscopic analysis; Static platelet adhesion

Human serum albumin adsorption on TiO 2 from single protein solutions and from plasma - Sousa, S.R.; Moradas-Ferreira, P.; Saramago, B.; Viseu Melo, L.; Barbosa, M.A. (LangmuirLangmuir, 2004)
In the present work, the adsorption of human serum albumin (HSA) on commercially pure titanium with a titanium oxide layer formed in a H 2O 2 solution (TiO 2 cp) and on TiO 2 sputtered on Si (TiO 2 sp) was analyzed. Adsorption isotherms, kinetic studies, and work of adhesion determinations were carried out. HSA exchangeability was also evaluated. Surface characterization was performed by atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and wettability studies. The two TiO 2 surfaces have very distinct roughnesses, the TiO 2 sp having a mean R a value 14 times smaller than the one of TiO 2 cp. XPS analysis revealed consistent peaks representative of TiO 2 on sputtered samples as well as on Ti cp substrate after 48 h of H 2O 2 immersion. Nitrogen was observed as soon as protein was present, while sulfur, present in disulfide bonds in HSA, was observed for concentrations of protein higher than 0.30 mg/mL. The work of adhesion was determined from contact angle measurements. As expected from the surface free energy values, the work of adhesion of HSA solution is higher for the TiO 2 cp substrate, the more hydrophilic one, and lower for the TiO 2 sp substrate, the more hydrophobic one. The work of adhesion between plasma and the substrates assumed even higher values for the TiO 2 cp surface, indicating a greater interaction between the surface and the complex protein solutions. Adsorption studies by radiolabeling of albumin ( 125I-HSA) suggest that rapid HSA adsorption takes place on both surfaces, reaching a maximum value after ~60 min of incubation. For the higher HSA concentrations in solution, a multilayer coverage was observed on both substrates. After the adsorption step from single HSA solutions, the exchangeability of adsorbed HSA molecules by HSA in solution was evaluated. The HSA molecules adsorbed on TiO 2 sp seem to be more easily exchanged by HSA itself than those adsorbed on TiO 2 cp after 24 h. In contrast, after 72 h, nearly all the adsorbed albumin molecules effectively exchange with other albumin molecules.
Cited By (since 1996): 58Export Date: 21 November 2012Source: ScopusCODEN: LANGDdoi: 10.1021/la049158dPubMed ID: 15491210Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; Inst. de Engenharia Biomédica, Laboratório Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: ssousa@ibmc.up.ptChemicals/CAS: serum albumin, 9048-46-8; titanium dioxide, 1317-70-0, 1317-80-2, 13463-67-7, 51745-87-0; titanium, 7440-32-6; Serum Albumin; Solutions; titanium dioxide, 13463-67-7; Titanium, 7440-32-6References: Nakabayashi, N., Iwasaki, Y., (2000) European White Book on Fundamental Research in Materials Science, pp. pp70-71. , Rühle, M., Dosch, H., Mittemeijer, E. J.Van de Voorde, M. H., Eds.; Max Plank Institut fur Metallforschung: Stuttgart, Germany;Windler, M., Klabunde, R., (2001) Titanium in Medicine; Material Science, Surface Science, Engineering, Biological Responses and Medical Applications, pp. 703-746. , Brunette, D. M., Tengvall, P., Textor, M., Thomsen, P., Eds.; Springer-Verlag: Berlin, Germany; Larsson, C., Esposito, M., Liao, H., Thomsen, P., (2001) Titanium in Medicine: Material Science, Surface Science, Engineering, Biological Responses and Medical Applications, pp. 587-648. , Brunette, D.M., Tengvall, P., Textor, M., Thomsen, P., Eds.; Springer-Verlag: Berlin, Germany; Tengvall, P., Lundstrom, I., (1992) Clin. Mater., 9, pp. 116-134; Ostumi, E., Chapman, R.G., Liang, M.N., Meluleni, G., Pier, G., Ingberg, D.E., Whitesides, G.M., (2001) Langmuir, 17, pp. 6336-6343; Gehanno, V., Freitas, P.P., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Soares, J.C., Silva, M.F., (1999) IEEE Trans. Magn., 35, pp. 4361-4367; Owens, D.K., Wendt, E.C., (1969) J. Appl. Polym. Sci., 13, pp. 1741-1747; Kerkeb, M.L., González-Caballero, F., Chibowski, E., (1993) J. Colloid Interface Sci., 159, pp. 439-443; (1993) A Guide to Radioiodination Techniques; Amersham Life Science: Little Chalfont, p. 64. , Iodine-125, Buckinghamshire, U.K; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, pp. 45-53; Williams, D.F., Askill, I.N., Smith, R., (1985) J. Biomed. Mater. Res., 19, pp. 313-320; Sheardown, H., Cornelius, R.M., Brash, J.L., (1997) Colloids Surf., B, 10, pp. 29-33; Du, Y.J., Cornelius, R.M., Brash, J.L., (2000) Colloids Surf., 17, pp. 59-67; Yu, X.J., Brash, J.L., (1993) Test Procedures for the Blood Compatibility of Biomaterials, pp. 287-330. , Dawids, S., Ed.; Kluwer Academic Publishers: Dordrecht, The Netherlands; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., (1985) Anal. Biochem., 150, pp. 76-85; Shirkhanzadeh, M., (1996) J. Mater. Sci.: Mater. Med., 6, pp. 206-210; Kilpadi, D.V., Raikar, G.N., Liu, J., Lemons, J.E., Vohra, Y., Gregory, J.C., (1998) J. Biomed. Mater. Res., 40, pp. 646-659; Lausmaa, J., Kasemo, B., Mattsson, H., (1990) Appl. Surf. Sci., 44, pp. 133-146; Armstrong, N.R., Quinn, R.K., (1977) Surf. Sci., 67, pp. 451-468; Leitao, E., Barbosa, M.A., Degroot, K., (1997) J. Mater. Sci.: Mater. Med., 8, pp. 423-426; Ramqvist, L., Hamrin, K., Johansso, G., Fahlman, A., Nordling, C., (1969) J. Phys. Chem. Solids, 30, pp. 1835-1847; Hanawa, T., Ota, M., (1992) Appl. Surf. Sci., 55, pp. 269-276; Kuznetsov, M.V., Zhuravlev, J.F., Gubanov, V.A., (1992) J. Electron Spectrosc. Relat. Phenom., 58, pp. 169-176; Ikeo, N., Iijima, Y., Niimura, N., Sigematsu, M., Tazava, T., Matsumoto, S., Kojima, K., Nagasawa, Y., (1991) Handbook of X-ray Photo-electron Spectroscopy JEOL, , Tokyo, Japan; Porte-Durrieu, M.C., Labrugere, C., Villars, F., Lefebvre, F., Dutoya, S., Guette, A., Bordenave, L., Baquey, C., (1999) J. Biomed. Mater. Res., 46, pp. 368-375; Wagner, C.D., Riggs, W.M., Davis, L.E., Moulder, J.F., (1979) Handbook of X-ray Photoelectron Spectroscopy, , Mulenberg, G. E., Ed.; Perkin Elmer Corp: Eden Prairie, MN; Barr, T.L., (1991) J. Vac. Sci. Technol., A, 9, pp. 1793-1805; Wälivaara, B., Aronsson, B.O., Rodahl, M., Lausmaa, J., Tengvall, P., (1994) Biomaterials, 15, pp. 827-834; Oji, M.O., Wood, J.V., Downes, S., (1999) J. Mater. Sci.: Mater. Med., 10, pp. 869-872; Pan, J., Liao, H., Leygraf, C., Thierry, D., Li, J., (1998) J. Biomed. Mater. Res., 40, pp. 244-256; Ratner, B.D., Horbett, T.A., Shuttleworth, D., Thomas, H.R., (1981) J. Colloid Interface Sci., 83, pp. 630-642; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interface Sci., 95, pp. 308-321; Auditore, A., Satriano, C., Coscia, U., Ambrosone, G., Parisi, V., Marietta, G., (2002) Biomol. Eng., 19, pp. 85-90; Miller, B., Treppo, S., Voigt, A., Zingg, W., Neumann, A.W., (1993) Colloids Surf., 69, pp. 203-208; Serro, A.P.V., Fernandas, A.C., Saramago, B.D.V., (1997) Colloids Surf., A, 125, pp. 209-219; Lopes, M., Monteiro, F., Santos, J., Serro, A., Saramago, B., (1999) J. Biomed. Mater. Res., 45, pp. 370-375; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, pp. 3105-3112; Vogler, E.A., (1993) Surfactant Science Series, 49, pp. 183-250. , Wettability; Berg, J. C., Ed.; Marcel Dekker: New York; Feng, B., Weng, J., Yang, B.C., Qu, S.X., Zhang, X.D., (2003) Biomaterials, 24, pp. 4663-4670; Morra, M., Cassinelli, C., Cascardo, G., Cahalan, P., Cahalan, L., Fini, M., Giardino, R., (2003) Biomaterials, 24, pp. 4639-4654; Wälivaara, B., Lundstrom, I., Tengvall, P., (1993) Clin. Mater., 12, pp. 141-148; Lincks, J., Boyan, B.D., Blanchard, C.R., Lohmann, C.H., Liu, Y., Cochran, D.L., Dean, D.D., Schwartz, Z., (1998) Biomaterials, 19, pp. 2219-2232; Ong, J.L., Carnes, D.L., Cardenas, H.L., Cavin, R., (1997) Implant Dent., 6, pp. 19-24; Ricci, J.L., Spivak, J.M., Blumenthal, N.C., (1991) The Bone Biomaterial Interface, pp. 334-349. , Davis, J. E., Ed.; University of Toronto Press: Toronto; Busscher, H.J., Vanpelt, A.W.J., Deboer, P., Dejong, H.P., Arends, (1984) J. Colloids Surf., 9, pp. 319-331; Hitchcock, S.J., Carroll, N.T., Nicholas, M.G., (1981) J. Mater. Sci., 16, pp. 714-732; Rakhorst, G., Van Der Mei, H.C., Van Oeveren, W., Spijker, H.T., Int, B.H.J., (1999) J. Artif. Organs, 22, pp. 35-39; Martins, M.C., Ratner, B.D., Barbosa, M.A., (2003) J. Biomed. Mater. Res., 67 A, pp. 158-171; Sigal, G.B., Mrksich, M., Whitesides, G.M., (1998) J. Am. Chem. Soc., 120, pp. 3464-3473; Prime, K.L., Whitesides, G.M., (1991) Science, 252, pp. 1164-1167; Vandulm, P., Norde, W., (1983) J. Colloid Interface Sci., 91, pp. 248-255; Williams, R.L., Williams, D.F., (1988) J. Colloid Interface Sci., 126, pp. 596-603; Serro, A.P.V.A., Fernandes, A.C., Saramago, B.D.V., Norde, W., (1999) J. Biomed. Mater. Res., 46, pp. 376-381; Norde, W., Anusiem, A.C.I., (1992) Colloids Surf., 86, pp. 73-80; Young, B.R., Pitt, W.G., Cooper, S.L., (1988) J. Colloid Interface Sci., 125, pp. 246-260; Feng, L., Andrade, J.D., (1994) Biomaterials, 5, pp. 323-333; Norde, W., (1986) Adv. Colloid Interface Sci., 25, pp. 267-340; Kurrat, R., Prenosil, J.E., Ramsden, J.J., (1987) J. Colloid Interface Sci., 186, pp. 1-8; Brash, J.L., Uniyal, S., Samak, Q., (1974) Trans. Am. Soc. Artif. Intern. Organs, 20 A, pp. 69-76
Keywords: Adsorption; article; Atomic force microscopy; Blood; chemistry; human; Human serum albumin (HSA); Humans; hydrophobicity; Multilayers; plasma; Plasmas; Plastic surgery; Proteins; Radiolabeling; Serum Albumin; solution and solubility; Solutions; Substrates; Surface characterization; Surface Properties; surface property; Titanium; Titanium dioxide; X ray photoelectron spectroscopy

"In vitro" bioactivity evaluation of CaO-P 2O 5 glass-hydroxylapatite thin coatings produced by pulsed laser deposition - Arias, J.L.; Liste, S.; González, P.; Serra, J.; León, B.; Ferraz, M.P.; Monteiro, F.J.; Giao, D.; Pérez-Amor, M. (Transactions - 7th World Biomaterials CongressTrans. World Biomater. Congr., 2004)
The synthesis of coatings based on hydroxyapatites (HA) and glass modified hydroxyapatite targets by pulsed laser deposition, was presented. It was observed that coatings produced from HA targets keep their crystallinity through all their thickness, while there is a loss of crystallinity towards the surface of the HA+1.5G coatings. On immersion in SBF for three days, the coatings produced from HA targets suffered a loss of crystallinity near the surfaces, while the crystallinity of the coatings produced from HA+1.5G targets increased. It was also observed that addition of 1.5wt% of CaO-P 2O 5 glasses to HA thin coatings produced by pulsed laser deposition leads to a significant structural change of the coating surface.
Conference code: 64310Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Arias, J.L.; Depto. de Física Aplicada, Universidade de Vigo, Lagoas-Marcosende 9, E-36200 Vigo, SpainReferences: Arias, J.L., (1997) J Mater Sci Mater Med, 8, p. 873;Ferraz, M.P., (1999) J Biomed Mater Res, 45, p. 373; Ferraz, M.P., (1999) J. Mat Sci Mat Med, 10, p. 567
Keywords: Apatites; Bioactivity; Calcium Compounds; Coatings; Crystalline materials; Crystalline phases; hydroxyapatite; Mixtures; Phosphorus Compounds; Pressure effects; Pulsed laser deposition; Scanning electron microscopy; Substrates; Thin coatings; X ray diffraction; X ray photoelectron spectroscopy

In Vitro Cytocompatibility of Osteoblastic Cells Cultured on Chitosan-Organosiloxane Hybrid Membrane - Shirosaki, Y.; Tsuru, K.; Hayakawa, S.; Osaka, A.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Chitosan-silicate hybrids were synthesized using γ-glycidoxypropyltrimethoxysilane (GPSM) as the agent to cross-link the chitosan chains. Fourier-transform infrared (PT-IR) spectroscopy was used to analyze the structures of the hybrids. The swelling ability and the cytocompatibility of the hybrids were investigated as a function of the GPSM concentration. The swelling of the hybrids was suppressed by addition of GPSM. MG63 human osteoblastic cells were cultured on the hybrids. The adhesion and proliferation of the MG63 cells cultured on the chitosan-GPSM hybrid surface were improved comparing to that on chitosan membrane, regardless the GPSM concentration.
Conference code: 62053Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Shirosaki, Y.; Biomaterial Laboratory, Faculty of Engineering, Okayama University, Tsushima, Okayama-shi 700-8530, JapanReferences: Chandy, T., Sharma, P.C., (1990) Biomat Art Cells Art Org, 18, pp. 1-24;Jameela, S.R., Jayakrishnan, A., (1995) Biomaterials, 16, pp. 769-775; Nishi, C., Nakajima, N., Ikada, Y., (1995) J Biomed Mater Res., 29, pp. 829-834; Ren, L., Tsuru, K., Hayajkawa, S., Osaka, A., (2002) Biomaterials, 23, pp. 4765-4773
Keywords: Biocompatibility; Biological membranes; biosynthesis; Cell culture; Cells; chitosan; Chitosan-inorganic hybrid; Crosslinking; Cytocompatibility; Fourier transform infrared spectroscopy; Nuclear magnetic resonance spectroscopy; Organic polymers; Osteoblastic cell (MG63); Structural analysis; Synthetic polymers; Tissue; Tissue engineering; γ-Glycidoxypropyltrimethoxysilane (GPSM)

In Vitro Mineralisation of Human Bone Marrow Cells Cultured on Bonelike® - Costa, M.A.; Gutierres, M.; Almeida, L.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Bonelike® is a CaO-P 2O 5 based glass-reinforced hydroxyapatite (HA) designed to mimic the inorganic composition of the bone tissue. This work evaluates the response of human bone marrow cells to Bonelike® concerning cell proliferation and osteoblast differentiation. HA was used as control material. Results showed that Bonelike® allowed the proliferation of bone marrow cells and their complete differentiation, as evidenced by the formation of cell-mediated mineralisation. In comparison with HA, Bonelike® had a positive effect on the expression of alkaline phosphatase and also on the formation of a mineralised matrix, two osteoblast markers.
Conference code: 62053Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Costa, M.A.; Inst. Cie. Blomed. de Abel Salazar, Universidade do Porto, Largo Abel Salazar, 4000 Porto, PortugalReferences: Santos, J.D., Campbell, J.K., Winston, G.H., European Patent N° WO0068164, 2000Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905;Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res.:App. Biomater., 48, p. 734; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Ferraz, M.P., Fernandes, M., Santos, J.D., Monteiro, F.J., (2001) J. Mat. Sci.: Mat. Med., 12, p. 629; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Duarte, F., Santos, J.D., Afonso, A., Advanced Materials Forum, , in press; Coelho, M.J., Fernandes, M.H., (2000) Biomaterials, 21, p. 1095; Kleerekoper, M., (1996) Principles of Bone Biology, p. 1053. , Academic Press
Keywords: Bone; Bonelike®; Cell culture; cell proliferation; Composition; Grafts; Human bone marrow cells; hydroxyapatite; In vitro mineralisation; mineralization; Scanning electron microscopy; Sintering; X ray diffraction

In Vivo Behaviour of Bonelike®/PLGA Hybrid: Histological Analysis and Peripheral Quantitative Computed Tomography (pQ-CT) Evaluation - Oliveira, J.M.; Kawai, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D.; Afonso, A. (Key Engineering MaterialsKey Eng Mat, 2004)
The present work consisted in assessing the in vivo biological behaviour of novel Bonelike®/PLGA hybrid materials through subcutaneous and tibiae implantations for a 4 week period using an animal model. No sign of inflammation was observed as a result of subcutaneous implantation, which reveals that these materials were well-tolerated by the soft tissues. pQ-CT analysis demonstrated that the implanted materials were highly osteointegrated in bone tissue. SEM analysis at bone defect area revealed that Bonelike® resorption occurred after 4 weeks of implantation. Although the osteoconductive properties of Bonelike® have been reported in literature, the present work allowed to demonstrate that the silane-coupling agent and the PLGA treatments do not significantly modify the biological performance of Bonelike®. This result is strongly encouraging since Bonelike®/PLGA hybrid materials are being developed for bone tissue healing/regeneration purposes with simultaneous delivery of therapeuthic molecules.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Oliveira, J.M.; Inst. de Engenharia Biomédica, Lab. de Biomaterials, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jmoliv@fe.up.ptReferences: Solheim, E., Pinholt, E., Bang, G., (1992) Journal Neurosurgery, 76, pp. 275-279;Laurecin, C.T., Attawia, M.A., Lu, L.Q., Borden, M.D., Lu, H.H., Gorum, W.J., Lieberman, J.R., (2001) Biomaterials, 22, pp. 1271-1277; Nielsen, F.F., Karring, T., Gogolewski, S., (1992) Acta Orthop Scandinavica, 63, pp. 66-69; Jiang, G., Woo, B.H., Kang, F., Singh, J., Deluca, P.P., (2002) Journal of Controlled Release, 79, pp. 137-145; Duarte, F., Lopes, M.A., Santos, J.D., European Cells and Materials, , in press; Duarte, F., Afonso, A., Santos, J.D., Advanced Materials Forum, , in press; Oliveira, J.M., Lopes, M.A., Kawai, T., Ohtsuki, C., Santos, J.D., Afonso, A., Advanced Materials Forum, , in press; Santos, J.D., Campbell, J.K., Winton, G.H., European Patent N° W00068164 (2000)Oliveira, J.M., Miyazaki, T., Lopes, M.A., Ohtsuki, C., Santos, J.D., Biomaterials, , submitted
Keywords: Biodegradation; Bonelike®; Computerized tomography; Histological analysis; histology; hydroxyapatite; In vivo studies; Organic polymers; PLGA; pQ-CT; Silanes; Sintering; Synthetic polymers; Tibiae implantations; Tissue

Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold - Barbosa, J.N.; Barbosa, M.A.A.; Águas, A.P. (BiomaterialsBiomaterials, 2004)
The acute inflammatory response and the adhesion of cells to self-assembled monolayers (SAMs) of well-defined surface chemistry was studied in vivo using a rodent air-pouch model of inflammation. SAMs with three different terminal functional groups (OH, COOH and CH 3) were implanted in subcutaneous air pouches induced in BALB/c mice. After 24h, inflammatory cells were recovered from the air pouches and the implants were removed and prepared for observation by scanning electron microscopy (SEM). The implants coated with OH and CH 3, were found to cause the highest recruitment of inflammatory cells into the subcutaneous pouches. Polymorphonuclear neutrophils (PMNs) leukocytes predominated over mononuclear cells in inflammatory exudates of SAMs-coated implants, the opposite being found in uncoated implants (controls). CH 3-coated implants induced the highest number of inflammatory cells and also the largest percentage of PMNs seen in the subcutaneous pouches. Control and OH-covered implants presented the higher densities of attached inflammatory cells detected by SEM. In contrast, the CH 3-coated implants showed a very low density of cells adherent to the implant surface. We conclude that the chemical nature and the degree of hydrophobicity of the surface of implants modulate both the local acute inflammatory reaction and the adhesion of leukocytes. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2003.09.047PubMed ID: 14751741Language of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomaterials, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: Gold, 7440-57-5; Sulfhydryl CompoundsReferences: Tang, L., Jiang, W., Welty, S.E., The participation of P- and E-selectins on biomaterial-mediated tissue responses (2002) J Biomed Mater Res, 62, pp. 471-477;Thomsen, P., Gretzer, C., Macrophage interactions with modified material surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Kao, W.J., Liu, Y., Gundloori, R., Li, J., Lee, D., Einerson, N., Burmania, J., Stevens, K., Engineering endogenous inflammatory cells as delivery vehicles (2002) J Control Release, 78, pp. 219-233; Anderson, J.M., Mechanisms of inflammation and infection with implanted devices (1993) Cardiovasc Pathol, 2, pp. 33S-41S; Anderson, J.M., Inflammatory response to implants (1988) ASAIO J, 11, pp. 101-107; Babensee, J.E., Anderson, J.M., McLntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliver Rev, 33, pp. 111-139; Mrksich, M., Whitesides, G.M., Interactions of SAMs with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrksich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Nuzzo, R.G., Allara, D.L., Adsorption of biofunctional organic dissulfides on gold surfaces (1983) J Am Chem Soc, 105, pp. 4481-4483; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiencies for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Castro, A.G., Esaguy, N., MacEdo, P.M., Águas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Isaji, M., Momose, Y., Naito, J., Enhancement of inflammatory reactions in a non-immunological air pouch model in rats (1989) Br J Exp Pathol, 70, pp. 705-716; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Hooper, K.A., Nickolas, T.L., Yurkow, E.J., Kohn, J., Laskin, D., Characterization of the inflammatory response to biomaterials using a rodent air pouch model (2000) J Biomed Mater Res, 50, pp. 365-374; Wooley, P.H., Morren, R., Andary, J., Sud, S., Yang, S., Mayton, L., Markel, D., Nasser, S., Inflammatory responses to orthopaedic biomaterials in the murine air pouch (2002) Biomaterials, 23, pp. 517-526; Gelb, H., Schumacher, H.R., Cuckler, J., Ducheyne, P., Baker, D.G., In vivo inflammatory response to polymethylmethacrylate particulate debris: Effect of size, morphology, and surface area (1994) J Orthop Res, 12, pp. 83-92; Wooley, P.H., Mayton, L., Sud, S., Nasser, S., Synergistic inflammatory responses to metallic and polymeric particles in the murine air pouch model of aseptic loosening (1996) Arthritis Rheum, 39, pp. 175-183; Moore, R., Beredjiklian, P., Rhoad, R., Theiss, S., Cuckler, J., Ducheyne, P., Baker, D.G., A comparison of the inflammatory potential of particulates derived from two composite materials (1997) J Biomed Mater Res, 34, pp. 137-147; Krause, T.J., Robertson, F.M., Greco, R.S., Measurement of intracellular hydrogen peroxide induced by biomaterials implanted in a rodent air pouch (1993) J Biomed Mater Res, 27, pp. 65-69; Yang, S., Ren, W., Park, Y., Sieving, A., Hsu, S., Nasser, S., Wooley, P.H., Diverse cellular and apoptotic responses to variant shapes of UHMWPE particles in a murine model of inflammation (2002) Biomaterials, 23, pp. 3535-3543; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkanethiols on gold surfaces (1997) Biomaterials, 18, pp. 1059-1068; Tengvall, P., Askendal, A., Lundsröm, I., Complement activation by 3-mercapto-1,2-propanediol immobilized on gold surfaces (1996) Biomaterials, 17, pp. 1001-1007; Liu, L., Elwing, H., Complement activation on thiol-modified gold surfaces (1996) J Biomed Mater Res, 30, pp. 535-541; Tang, L., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Källtorp, M., Oblogina, S., Jacobsson, S., Karlsson, A., Tengvall, P., Thomsen, P., In vivo cell recruitment, cytokine release and chemiluminescence response at gold, and thiol functionalized surfaces (1999) Biomaterials, 20, pp. 2123-2137; Tang, L., Ugarova, T.P., Plow, E.F., Eaton, J.W., Molecular determinants of acute inflammatory responses to biomaterials (1997) J Clin Invest, 97, pp. 1329-1334; Hu, W., Eaton, J.W., Tang, L., Molecular basis of biomaterial-mediated foreign body reactions (2001) Blood, 98, pp. 1231-1238; Silver, J.H., Hergenrother, R.W., Lin, J., Lim, F., Lin, H., Okada, T., Chaudhury, M.K., Cooper, S.L., Surface and blood-contacting properties of alkylsiloxane monolayers supported on silicone rubber (1995) J Biomed Mater Res, 29, pp. 535-548; Werthén, M., Sellborn, A., Källtorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Tang, L., Eaton, J.W., Fibrin(ogen) mediates acute inflammatory responses to biomaterials (1993) J Exp Med, 178, pp. 2147-2156; Liu, L., Elwing, H., Complement activation on solid surfaces as determined by C3 deposition and hemolytic consumption (1994) J Biomed Mater Res, 28, pp. 767-773; Tengvall, P., Askendal, A., Lundstrom, I., Complement activation by IgG immobilized on methylated silicon (1996) J Biomed Mater Res, 31, pp. 305-312; Källtorp, M., Askendal, A., Thomsen, P., Tengvall, P., Ellipsometric studies in vitro on kinetics of rat complement activation (1999) J Biomed Mater Res, 44, pp. 222-225; Barbosa, J.N., Barbosa, M.A., Águas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res, 65, pp. 429-434
Keywords: Air-pouch model; alkane derivative; animal cell; animal experiment; animal model; Animals; article; Biomaterials; cell adhesion; Cell culture; cell density; cell surface; Cell-surface interactions; controlled study; exudate; gold; gold complex; hydrophobicity; implantation; Inflammation; Inflammatory responses; leukocyte; Leukocytes; male; material coating; Mice; Mice, Inbred BALB C; Microscopy, Electron, Scanning; mouse; neutrophil; nonhuman; polymorphonuclear cell; priority journal; Rodentia; Scanning electron microscopy; Self assembly; Self-assembled monolayers; Sulfhydryl Compounds; Surface chemistry; surface property

Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of HA suspensions - Lemos, A.F.; Santos, J.D.; Ferreira, J.M.F. (Materials Science ForumMater Sci Forum, 2004)
In order to evaluate how the characteristics of starting HA powders affect their dispersion ability, several tests were made, including particle size distribution, particle morphology (SEM) and rheological measurements of the suspensions. To enable the preparation of concentrated suspensions as high as possible, the influence of deagglomeration procedure on rheological behaviour of hydroxyapatite aqueous suspensions was evaluated. The results revealed significant differences in the dispersing ability of the powders and on the maximum achievable solids loading. In fact, the maximum solids volume fraction that was possible to incorporate in the initial suspension of HA R was only 35-vol.%, while with the HA S it has been possible to start from 45-vol.% suspensions. Ball milling revealed to be more efficient than planetary milling in the preparation of HA R suspensions, and enabled to achieve a maximum solids volume fraction of 45-vol.% at the end of long milling period, which included successive incremental additions of powder. The powder HA S exhibited a much better dispersing ability, enabling the preparation of 60-vol.% solids only after two hours of planetary milling.
Conference code: 63332Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Ferreira, J.M.F.; Dept. of Ceramics Engineering, CICECO, Univ. of Aveiro, 3810-193 Aveiro, Portugal; email: jmf@cv.ua.ptReferences: Kanazawa, T., (1989) Inorganic Phosphate Materials, 52, p. 15. , Materials Science Monographs, (Elsevier Science Publishers, Amsterdam);Elliot, J.C., (1994) Structure and Chemistry of the Apatites and Other Calcium Orthophosphates. Studies in Organic Chemistry, 18. , Elsevier Science, Netherlands; Ohgushi, H., Okumura, M., Yoshikawa, T., Inoue, K., Senpuku, N., Tamai, S., Shors, E.C., (1992) J. Biomed. Mater. Res., 26, p. 885; Saggio-Woyanski, J., Scott, C., (1992) Am. Ceram. Soc. Bull., 71, p. 1674; Lyckfeldt, O., Ferreira, J.M.F., (1998) J. Eur. Ceram. Soc., 18, p. 131; Lorenzo, L.M.R., (1999), PhD Thesis MadridOlhero, S.M., Ferreira, J.M.F., (2003) Powder Thecnology, , accepted for publication
Keywords: Agglomeration; Bioceramics; crystallography; Deagglomeration; Foaming processes; hydroxyapatite; medicine; morphology; Particle size analysis; Powder characteristics; Powders; rheology; Scanning electron microscopy; Sedimentation; Sintering

Laser surface modification of hydroxyapatite and glass-reinforced hydroxyapatite - Queiroz, A.C.; Santos, J.D.; Vilar, R.; Eugénio, S.; Monteiro, F.J. (BiomaterialsBiomaterials, 2004)
Surface treatment of materials with excimer laser radiation often results in the formation of a rough columnar or cone-shaped surface topography, which leads to a considerable increase in the surface area. As a result, the search for a non-porous bioactive material with adequate mechanical properties and a high surface to volume ratio, similar to porous materials, which could be used for drug delivery in the treatment of periodontitis, justified assessing excimer laser surface treatment to promote controlled roughning of hydroxyapatite (HA) and glass-reinforced hydroxyapatite (GR-HA). A KrF excimer laser with 248nm radiation wavelength and 30ns pulse duration was used for surface modification. The laser treatment was carried out in air, using wide ranges of radiation fluence and number of laser pulses. In order to identify the physico-chemical changes induced by the laser treatment and the column formation mechanisms in these materials, the treated surfaces were characterised by laser profilometry, scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier transform infra-red spectroscopy (FTIR). Laser processing induced the formation of a surface topography consisting of cone-shaped features. The constitution of the surface layer was also modified, as revealed by FTIR, XPS and XRD. This work has shown that laser surface modification increases the surface area of HA and GR-HA and is a promising technique to increase the reactivity and drug delivery capability of both materials. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2003.11.054PubMed ID: 15120506Language of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB-Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180, Porto, Portugal; email: aqueiroz@ineb.up.ptChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; Biocompatible Materials; Durapatite, 1306-06-5; Macromolecular SubstancesReferences: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., Clinical evaluation of porous and nonporous hydroxyapatite in the treatment of human periodontal bony defects (1987) J Periodontol, 58, pp. 521-528;Seymour, R.A., Heasman, P.A., MacGregor, I.D.M., The pathogenesis of periodontal disease (1992) Drugs, Diseases, and the Periodontium, pp. 1-10. , I.D.M. MacGregor. Oxford: Oxford University Press; Systemic antibiotics in periodontics (1996) J Periodontol, 67, pp. 831-838; Steinberg, D., Friedman, M., Soskolne, A., Sela, M.N., A new degradable controlled release device for treatment of periodontal disease: In vitro release study (1990) J Periodontol, 61, pp. 393-398; Soskolne, W.A., Heasman, H.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., Sustained local delivery of chlorhexidine in the treatment of periodontitis: A multi-center study (1997) J Periodontol, 68, pp. 32-38; Prado Da Silva, M.H., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., Porous glass reinforced hydroxyapatite materials produced with different organic additives (2002) J Non-Cryst Solids, 304, pp. 286-292; Barinov, S.M., Baschenko, Y.V., Application of ceramic composits as implants: Result and problem (1992) Bioceramics and the Human Body, pp. 206-210. , A. Krajewski. UK: Elsevier Science Publishers; Koshino, T., Murase, T., Takagi, T., Saito, T., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; Nishihara, K., Studies on peri-root tissue formation around new type artificial root made of dense hydroxyapatite (1993) Clin Mater, 12, pp. 159-167; Chang, B., Lee, C., Hong, K., Youn, H., Ryu, H., Chung, S., Park, K., Osteoconduction at porous hydroxyapatite with various pore configurations (2000) Biomaterials, 21, pp. 1291-1298; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tensions, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO (1996) J Mater Sci: Mater Med, 7, pp. 187-189; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of effects of glass on response of osteosarcoma cells to plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings (1999) J Biomed Mater Res, 47, pp. 603-611; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P2O5 Glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., Adsorption and release of sodium ampicillin from hydroxyapatite and glass-reinforced hydroxyapatite composites (2001) Biomaterials, 22, pp. 1393-1400; Clèries, L., Fernández-Pradas, J.M., Morenza, J.L., Behaviour in simulated body fluid of calcium phosphate coating obtained by laser ablation (2000) Biomaterials, 21, pp. 1861-1865; D'Alession, L., Teghil, R., Zaccardo, I., Ferro, D., Marotta, V., Pulsed laser ablation and deposition of bioactive glass as coating material for biomedical applications (1999) Appl Surf Sci, 138-139, pp. 527-532; Fernández-Pradas, J.M., Clèries, L., Serra, P., Sardin, G., Morenza, J.L., Evolution of the depositon rate during pulsed laser deposition of hydroxyapatite coatings and its relation with target morphology (2001) Appl Phys a, 72, pp. 613-618; Zeng, H., Lacefield, W.R., XPS, EDX and FTIR analysis of pulsed laser deposited calcium phosphate bioceramic coatings: The effects of various process parameters (2000) Biomaterials, 21, pp. 23-30; Serra, P., Fernández-Pradas, J.M., Sardin, G., Morenza, J.L., Interaction effects of an excimer laser beam with hydroxyapatite targets (1997) Appl Surf Sci, 109-110, pp. 384-388; Serra, P., Morenza, J.L., Fluence dependence of hydroxyapatite laser ablantion plumes (1998) Thin Solid Films, 335, pp. 43-48; Foltyn, S.R., Dye, R.C., Ott, K.C., Peterson, E., Hubbard, K.M., Hutchinson, W., Muenchausen, R.E., Wu, X.D., Target modification in the excimer laser deposition of YBa 2Cu 3O 7-x thin films (1991) Appl Phys Lett, 59, pp. 594-596; Oliveira, V., Conde, O., Vilar, R., UV laser micromachining of ceramic materials: Formation of columnar topographies (2001) Adv Eng Mater, 3, pp. 75-81; Ricci, J.L., Alexander, H., Laser microtexturing of implant surfaces for enhanced tissue integration (2001) Key Eng Mater, 198-199, pp. 179-202; Khor, K.A., Vreeling, A., Dong, Z.L., Cheang, P., Laser treatment of plasma sprayed HA coatings (1999) Mater Sci Eng a, 266, pp. 1-7; Sobol, E.M., (1995) Phase transformations and ablation in laser-treated solids, , New York: Wiley; Underwood, E.E., (1970) Quantitative Stereology, , Reading: Addison-Wesley;; Underwood, E.E., Banerji, K., Quantitative fractography (1987) ASM-Metals Handbook, 12; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 4 PO 4 3- domain (1990) Calcif Tissue Int, 46, pp. 384-394; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., Resolution enhanced Fourier transform infrared spectroscopy study of the environment of phosphate ion in the early deposits of a solid phase calcium phosphate in bone and enamel and their evolution with age: Investigations in the ν 3 PO 4 3- domain (1991) Calcif Tissue Int, 49, pp. 383-388; Elliott, J.C., Structure and chemistry of apatites and other calcium orthophosphates (1994) Inorganic Chemistry, 18, p. 50. , Elliott J.C. Amsterdam: Elsevier Science; Dupraz, A., Nguyen, T.P., Richard, M., Dalcusi, G., Passuti, N., Influence of a cellulosic ether carrier on the structure of biphasic calcium phosphate ceramic particles in an injectable composite material (1999) Biomaterials, 20, pp. 663-673; Franke, R., Chassé, Th., Streubel, P., Meisel, A., Auger parameters and relaxation energies of phosphorus in solid compounds (1991) J Electron Spectrosc Relat Phemon, 56, pp. 381-388; Heitz, J., Pedarning, J.D., Bauerle, D., Petzow, G., Excimer laser ablation and micro-patterning of ceramic Si 3N 4 (1997) Appl Phys a, 65, pp. 259-261; Foltyn, S.R., Surface modification of materials by cumulative laser irradiation (1994) Pulsed Laser Deposition of Thin Films, pp. 89-113. , D.B. Chrisey, & G.K. Hubler. New York: Wiley; Lappalainen, J., Frantti, J., Lanto, V., Surface structure and particulate generation in Pb 0.97Nd 0.02(Zr 0.55Ti 0.45)O 3 ablation targets during pulsed laser deposition (1999) J Am Cer Soc, 82, pp. 889-896; Óbrien, T.P., Lawler, J.F., Lunney, J.G., Blau, W.J., The effect of laser fluence on the ablation and deposition of YBa 2Cu 3O 7 (1992) Mater Sci Eng, 13, pp. 9-13; Man, H.C., Zhang, X.M., Yue, T.M., Lau, W.S., Excimer-laser surface modification of engineering ceramics for adhesive bonding (1997) J Mater Proc Techn, 66, pp. 123-129; Sánchez, F., Morenza, J.L., Trtik, V., Characterization of the progressive growth of columns by excimer laser irradiation of silicon (1999) Appl Phys Lett, 75, pp. 3303-3305; Pedraza, A., Fowlkes, J.D., Lowndes, D.H., Self organized silicon microcolumns arrays generated by pulsed laser irradiation (1999) Appl Phys a, 69, pp. 731-S734; Usoskin, A., Freyhardt, H.C., Krebs, H.U., Influence of light scattering on the development of laser induced ridge-cone structure on target surfaces (1999) Appl Phys a, 69, pp. 823-S826
Keywords: article; Biocompatible Materials; Biomaterials; drug delivery system; Durapatite; Excimer laser; Excimer lasers; Fourier transform infrared spectroscopy; FTIR; glass; hydroxyapatite; infrared spectroscopy; laser; Lasers; Macromolecular Substances; materials testing; Molecular Conformation; Non-porous bioactive materials; periodontitis; physical chemistry; porosity; priority journal; Profilometry; Radiation Dosage; Reinforcement; Scanning electron microscopy; Surface area; Surface modification; Surface Properties; Surface treatment; topography; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; XPS; XRD

Mineralised membranes for bone regeneration - Mesquita, P.; Branco, R.; Afonso, A.; Vasconcelos, M.; Cavalheiro, J. (Key Engineering MaterialsKey Eng Mat, 2004)
Guided bone regeneration can be achieved using filling biomaterials and protective membranes. The aim of this work is to study a new membrane prepared from shrimp shells, without modification of the natural concave shape. The "in vitro" bioactivity was evaluated using a simulated body fluid prepared with substitution of calcium by strontium (SBR-Sr). The bioactivity behaviour was increased using a surface treatment with sodium silicate. The "in vitro" and "in vivo" tests allow to conclude that these membranes are bioactive and can induce bone growth on their surfaces.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Mesquita, P.; Inst. de Engenharia Biomédica, R. do Campo Alegre 823, 4150-180 Porto, PortugalReferences: Baron, M., Haas, R., Dörtbudak, O., Watzek, G., Experimentally induced peri-implantitis: A review (2000) Int J Oral Maxillofac Implants, 15, pp. 533-544;Hammerle, C.H., Jung, R.E., Feloutzis, A., A systematic review of the survival of implants in bone sites augmented with barrier membranes (guided bone regeneration) in partially edentulous patients (2002) J Clin. Periodontol., 29 (SUPPL. 3), pp. 226-231; Brunel, G., Brocard, D., Duffort, J.F., Jacquet, E., Justumus, P., Simonet, T., Benque, E., Bioabsorbable materials for guided bone regeneration prior to implant placement and 7-year followup: Report of 14 cases (2001) J Periodontol., 72 (2), pp. 257-264; Karapati, S., Hugson, A., Kugelberg, C.F., Healing following GTR treatment of bone defects distal to mandibular 2 nd molars after removal of impacted 3 rd molars (2000) J. Clin. Periodontol., 27, pp. 325-332; Simões, R., Fonseca, L., Vasconcelos, M., Afonso, A., Cavalheiro, J., Modified exoskeleton of shrimp for guided bone regeneration (2002) 17 th ESB, , Barcelona, Spain, September
Keywords: Biological membranes; biomaterial; Biomaterials; Bone; Bone Regeneration; Calcium; Ceramic materials; Deproteinization; Membrane; Mineralised membranes; Natural material; Optical microscopy; Shear strength; Sodium compounds; Strontium; Substitution reactions

A model for educational simulation of infant cardiovascular physiology - Goodwin, J.A.; van Meurs, W.L.; Sá Couto, C.D.; Beneken, J.E.W.; Graves, S.A. (Anesthesia and AnalgesiaAnesth. Analg., 2004)
Full-body patient simulators provide the technology and the environment necessary for excellent clinical education while eliminating risk to the patient. The extension of simulator-based training into management of basic and critical situations in complex patient populations is natural. We describe the derivation of an infant cardiovascular model through the redefinition of a complete set of parameters for an existing adult model. Specifically, we document a stepwise parameter estimation process, explicit simplifying assumptions, and sources for these parameters. The simulated vital signs are within the target hemodynamic variables, and the simulated systemic arterial pressure wave form and left ventricular pressure volume loop are realistic. The system reacts appropriately to blood loss, and incorporation of aortic stenosis is straightforward. This infant cardiovascular model can form the basis for screen-based educational simulations. The model is also an essential step in attaining a full-body, model-driven infant simulator.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: AACRAdoi: 10.1213/01.ANE.0000134797.52793.AFPubMed ID: 15562049Language of Original Document: EnglishCorrespondence Address: Goodwin, J.A.; Nemours Children's C., 807 Children's Way, Jacksonville, FL 32207, United States; email: jgoodwin@nemours.orgReferences: Good, M.L., Gravenstein, J.S., Training for safety in an anesthesia simulator (1993) Semin Anesth, 12, pp. 235-250;Gaba, D.M., DeAnda, A., The response of anesthesia trainees to simulated critical incidents (1989) Anesth Analg, 68, pp. 444-451; Howard, S.K., Gaba, D.M., Fish, K.J., Anesthesia crisis resource management training: Teaching anesthesiologists to handle critical incidents (1992) Aviat Space Environ Med, 63, pp. 763-770; Euliano, T.Y., Caton, D., Van Meurs, W., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) J Clin Monit, 13, pp. 293-297; Halamek, L.P., Kaegi, D.M., Gaba, D.M., Time for a new paradigm in pediatric medical education: Teaching neonatal resuscitation in a simulated delivery room environment (2000) Pediatrics, 106, pp. E45; Beneken, J.E.W., (1965) A Mathematical Approach to Cardiovascular Function: The Uncontrolled Human System, , [PhD thesis]. Medisch Fysisch Institut TNO, Utrecht, The Netherlands; Beneken, J.E.W., DeWit, B., A physical approach to hemodynamic aspects of the human cardiovascular system (1967) Physical Bases of Circulatory Transport: Regulation and Exchange, pp. 1-45. , Reeve EB, Guyton AC, eds. Philadelphia: Saunders; Wesseling, K.H., Settels, J.J., Baromodulation explains short-term blood pressure variability (1985) Psychophysiology of Cardiovascular Control, pp. 69-97. , Orlebeke JF, Mulder G, van Doornen LJP, eds. New York: Plenum Press; Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324; Pruitt, A.W., Gersony, W.M., The cardiovascular system (1992) Nelson Textbook of Pediatrics. 14th Ed., pp. 1125-1227. , Behrman RE, ed. Philadelphia: Saunders; Gregory, G.A., Monitoring during surgery (1994) Pediatric Anesthesia, pp. 261-279. , Gregory GA, ed. New York: Churchill Livingstone; Graham Jr., T.P., Jarmakani, M.M., Evaluation of ventricular function in infants and children (1971) Pediatr Clin North Am, 18, pp. 1109-1132; Wodey, E., Plady, P., Copin, C., Comparative hemodynamic depression of sevoflurane versus halothane in infants (1997) Anesthesiology, 87, pp. 795-800; Suga, H., Sagawa, K., Shoukas, A.A., Load independence of the instantaneous pressure-volume ratio of the canine left ventricle and effects of epinephrine and heart rate on the ratio (1973) Circ Res, 2, pp. 314-322; Ten Voorde, B., (1992) Modeling the Baroreflex: A System Analysis Approach, , [PhD thesis]. Vakgroep Medische Fysica, Amsterdam, The Netherlands; Cunningham, M.D., Bedside pulmonary function testing of infants (1990) Essentials of Pediatric Intensive Care, pp. 878-883. , Levin DL, Morriss FC, eds. St. Louis: Quality Medical; Strafford, M.A., Cardiovascular physiology (1996) Smith's Anesthesia for Infants and Children, pp. 69-104. , Motoyama EK, Davis PJ, eds. St. Louis: Mosby; Lake, C.L., Cardiovascular anatomy and physiology (1992) Clinical Anesthesia, pp. 989-1020. , Barash PG, Cullen BF, Stoelting RK, eds. Philadelphia: Lippincott; Hsieh, K., Chen, P., Fu, S., A simple, noninvasive method to investigate vascular characteristics in children (1996) Angiology, 47, pp. 361-367; Stoelting, R.K., Miller, R.D., (2000) Basics of Anesthesia, pp. 364-375. , Philadelphia: Churchill Livingstone; Thilenius, O.G., Argilla, R.A., Angiographic right and left ventricular volume determination in normal infants and children (1974) Pediatr Res, 8, pp. 67-74; Drouin, E., Gournay, V., Calamel, J., Assessment of spontaneous baroreflex sensitivity in neonates (1997) Arch Dis Child Fetal Neonatal Ed, 76, pp. F108-12
Keywords: aging; Algorithms; Anesthesiology; aorta stenosis; Aortic Valve Stenosis; arterial pressure; article; Baroreflex; biological model; bleeding; Blood Loss, Surgical; cardiovascular function; Cardiovascular physiology; Computer simulation; education; heart ventricle pressure; hemodynamic parameters; Hemodynamic Processes; Humans; Infant; Models, Biological; priority journal; Pulmonary Circulation; simulation; Ventricular Function, Left; Ventricular Function, Right

New Method for the Incorporation of Soluble Bioactive Glasses to Reinforce Porous HA Structures - Lemos, A.F.; Santos, J.D.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2004)
The most widely used calcium-phosphate ceramic in clinical applications is hydroxyapatite, Ca 10(PO 4) 6(OH) 2, however its dissolution rate in the human body after implantation is too low to achieve good results and it has poor mechanical properties. Recently, glass reinforced hydroxyapatite composites (GR-HA) have been developed, in order to improve the mechanical properties and to increase the similarity between implants and bone. The addition of a P 2O 5 based glass to a hydroxyapatite matrix, promotes the liquid phase sintering, improving the mechanical properties of the final bodies, and enabling the formation of two other calcium-phosphate phases, which have a higher dissolution rate, more compatible with bone regeneration. However, some of these glass compositions are soluble in water, making their incorporation in aqueous slurry impossible. Therefore, the aim of the present work is to study a new alternative method for the incorporation of soluble P 2O 5 based glass into macroporous structures obtained by different methods.
Conference code: 62053Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Lemos, A.F.; Dept. of Ceramic Engineering, University of Aveiro, Campus de Santiago, 3810-193 Aveiro, Portugal; email: ilemos@cv.ua.ptReferences: De Groot, K., (1983) Bioceramics of Calcium Phosphates, , CRC Press, Boca Raton, FL;Wilson, L.L., Hench, J., (1993) An Introduction to Bioceramics, , World Scientific, UK; Hench, L.L., (1998) J. Am. Ceram. Soc., 81, p. 1075; Kohri, M., Miki, K., Waite, D.E., Nakajima, H., Okabe, T., (1993) Biomaterials, 14, p. 299; Krivak, N., Tas, A.C., (1998) J. Am. Ceram. Soc., 81, p. 2245; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., (2003) Advanced Materials Forum
Keywords: Bioactivation; Bioactive glass; Biocompatibility; Bone; Dissolution; glass; hydroxyapatite; Liquid phase sintering; Macroporous structures; Microstructure; Porous materials; Reinforced hydroxyapatite; Sintering; Slurries

Porous Hydroxyapatite and Glass Reinforced Hydroxyapatite for Controlled Release of Sodium Ampicillin - Queiroz, A.C.; Teixeira, S.; Santos, J.D.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2004)
Porous hydroxyapatite (HA) and glass reinforced hydroxyapatite (GRHA) with adequate macro and microporous structure were developed, aiming at being used as drug delivery carrier of antibiotics, for the in situ treatment of periodontitis. Materials were characterised by XRD and FTIR, presenting no changes from similar dense materials. Mercury intrusion porosimetry revealed micropores of less than 1 μm, accounting for 15% of the total porosity. Compression tests have shown close values for HA and GRHA, with the former showing slightly higher values of strength. Ampicillin adsorption was more effective on porous than on dense HA, and was similar for HA and GRHA.
Conference code: 62053Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: aqueiroz@ineb.up.ptReferences: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., (1987) J Periodontol, 58, pp. 521-528;Seymour, R.A., Heasman, P.A., MacGregor, I.D.M., The pathogenesis of periodontal disease (1992) Drugs, Diseases, and the Periodontium, pp. 1-10. , MacGregor IDM, editor. Oxford: Oxford University Press; Steinberg, D., Friedman, M., Soskolne, A., Sela, M.N., (1990) J Periodontol, 61, pp. 393-398; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., (1996) J Mater Sci: Mater Med, 7, pp. 187-189; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J Biomed Mat Res, 45, pp. 376-383; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Key Engineering Materials, , submitted; Nishihara, K., (1993) Clin Materials, 12, pp. 159-167; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., (2001) Biomaterials, 22, pp. 1393-1400
Keywords: Adsorption; Antibiotics; Coatings; Dense materials; Diseases; Drug delivery; Drug dosage; Fourier transform infrared spectroscopy; glass; Glass reinforced hydroxyapatite; hydroxyapatite; Mercury (metal); Porous; Porous materials; Scanning electron microscopy; Sodium; Strength of materials; Ultraviolet spectroscopy; X ray diffraction analysis

Preparation and Characterization of Calcium Phosphate Nanoparticles - Manuel, C.M.; Foster, M.; Monteiro, F.J.; Ferraz, M.P.; Doremus, R.H.; Bizios, R. (Key Engineering MaterialsKey Eng Mat, 2004)
In this work, CaP nanoparticles were prepared by wet chemical precipitation using three different approaches and were characterised and quantified in terms of their composition. Different precipitating, ageing and drying temperatures were applied and affected HA to TCP ratio. Sintering induced formation of large agglomerates and affected the relative composition, specifically, increased concentrations of TCP as proved by SEM, FTIR and XRD. Different reactants also affected chemical final product composition. Contacts with fibroblasts and osteoblasts revealed better adhesion to sintered substrates.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Manuel, C.M.; Inst. de Engenharia Biomédica, Lab. de Biomaterials, Universidade do Porto, Rua do Campo Alegre, 823, 4150 -180 Porto, Portugal; email: cmmanuel@fe.up.ptReferences: Manuel, C.M., Ferraz, M.P., Monteiro, F.J., (2003) Key Engineering Materials, pp. 240-242;Jarcho, M., Bolen, C.H., Thomas, M.B., Bobick, J., Doremus, R.H., (1976) J Mat Sci, pp. 2027-2035; Jarcho, M., Salsbury, R.L., Thomas, M.B., Doremus, R.H., (1979) J Mat Sci, pp. 142-150; Puleo, D.A., Holleran, L.A., Doremus, R.H., Bizios, R., (1991) J Biomed Mat Res, 25, pp. 711-723; Fowler, B.O., Moreno, E.C., Brown, W.E., (1966) Arch. Oral Biol., 11, pp. 477-492
Keywords: Agglomeration; Bioceramics; Biocompatibility; Bone; Calcium Compounds; Cell culture; Cytocompatibility; Fourier transform infrared spectroscopy; hydroxyapatite; nanoparticles; Nanostructured materials; orthopedics; Precipitation (chemical); Scanning electron microscopy; Synthesis (chemical); Tricalcium phosphate; Wet chemical precipitation; X ray diffraction analysis

Production of porous hydroxyapatite with potential for controlled drug delivery - Queiroz, A.C.; Teixeira, S.; Santos, J.D.; Monteiro, F.J. (Materials Science ForumMater Sci Forum, 2004)
Porous hydroxyapatite was prepared in order to be used as a drug carrier and promote bone ingrowth. For this purpose, the microstructure should have interconnective pores and micro as well as macro porosity, for bone cell adhesion and bone ingrowth. The porous hydroxyapatite prepared by the burn-out method exhibits all these features. For measuring porosity, SEM analysis, mercury intrusion porosimetry and BET were used. FT-IR and XRD analysis revealed that only hydroxyapatite phase was present, being this result similar to the one found for dense samples. The morphology obtained appears to be well adapted to bone growth and drug adsorption.
Conference code: 63332Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Queiroz, A.C.; INEB, Inst. de Engenharia Biomédica, R do Campo Alegre, 823, 4150-180 Porto, Portugal; email: aqueiroz@ineb.up.ptReferences: Krejci, C.B., Bissada, N.F., Farah, C., Greenwell, H., (1987) J. Periodontology, 58, p. 521;Seymour, R.A., Heasman, P.A., MacGregor, I.D.M., The pathogenesis of periodontal disease (1992) Drugs, Diseases, and the Periodontium, , Oxford University Press; (1996) Journal of Periodontology, 67, p. 831; Soskolne, W.A., Heasman, H.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., (1997) Journal of Periodontology, 68, p. 32; Da Silva, M.H.P., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., (2002) J. of Non-crystaline Solids, 304, p. 286; Chang, B., Lee, C., Hong, K., Youn, H., Ryu, H., Chung, S., Park, K., (2000) Biomat., 21, p. 1291; Ewers, R., Simons, B., (1992) Biomaterials - Hard Tissue Repair and Replacement, , Elsevier Sc; Ohgushi, H., Okumura, M., Yoshikawa, T., Inoue, K., Senpuku, N., Tamai, S., Shors, E.C., (1992) Journal of Biomedical Materials Research, 26, p. 885; Barinov, S.M., Baschenko, Y.V., (1992) Bioceramics and the Human Body, , Elsevier Sc; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., (1997) J. Mater. Sc.: Materials in Medicine, 8, p. 731; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., (2003) Bioceramics, , accepted for; Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., (2001) Biomaterial, 22, p. 1393
Keywords: Adsorption; Antibiotics; Bioceramics; Controlled drug delivery; Drug Carriers; Drug delivery; Fourier transform infrared spectroscopy; hydroxyapatite; morphology; Polyurethanes; porosity; Porous; Porous materials; Scanning electron microscopy; X ray diffraction analysis

Protein adsorption effect on in vitro acellular biodegradation of CaO-P 2O 5 glass ceramics - Dias, A.G.; Lopes, M.A.; Santos, J.D. (Materials Science ForumMater Sci Forum, 2004)
This work reports the in vitro accelular behaviour of a glass ceramic (45P 2O 5-45CaO-5MgO-5K 2O), which has significant potential for being used as an alloplastic bone graft. Experiments were carried out by immersing granule samples for a period up to 90 days in Trisbuffer solution at pH 7.4, in the presence and absence of a foetal bovine serum (FBS). The release of calcium, phosphorus, and potassium ions as well as the amount of protein adsorbed was followed by several techniques. The results obtained seem to indicate that the adsorption of proteins on the surface of the material, although causing an initial delay in the degradation, does not hamper the ionic exchange and therefore it is not a barrier for the degradation of the glass ceramic.
Conference code: 63332Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Zeng, Chittur, K.K., Lacefield, W.R., (1999) Biomaterials, 20, p. 377;Ohta, Monna, H., Takahashi, S., (2001) J. Biomed. Mater. Res., 55, p. 409; Zyman, Z., Dedukh, N.V., Glusko, V.I., Shcherbyna, S.V., (2002) 17 th European Society for Biomaterials Conference Proceedings, , Barcelona; Krajewski, Malavoti, R., Piancatelli, A., (1996) Biomaterials, 17, p. 53; El-Ghannam, Ducheyne, P., Shapiro, I.M., (1997) Biomaterials, 18 (4); Takami, (1998) J. Biomed. Mater. Res., 40, p. 24; Puleo, A., Bizios, R., (1992) J. Biomed. Mater. Res., 26, p. 291; Dubois, C., Souchier, C., Couble, M.L., Exbrayat, P., Lissac, M., (1999) Biomat., 20, p. 1841; Green, J., Davies, M.C., Roberts, C.J., Tendler, S.J.B., (1997) Biomaterials, 18, p. 405; Haynes, C.A., Norde, W., (1994) Colloids and Surfaces B: Biointerfaces, 2, p. 517; Dias, G., Lopes, M.A., Gibson, I.R., Santos, J.D., (2002) 17 th Europ. Soc. for Biomat. Conf. Proc., , Barcelona; Chun, Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., (2002) Key Eng. Mat., 218-220, p. 149
Keywords: Adsorption; Bioceramics; Biodegradation; Calcium Compounds; Foetal bovine serum (FBS); Glass ceramics; Hard tissue; Ion exchange; Ionic strength; pH effects; Protein adhesion; Proteins; Tissue

Protein electrostatic self-assembly on poly(DL-lactide) scaffold to promote osteoblast growth - Zhu, H.; Ji, J.; Barbosa, M.A.; Shen, J. (Journal of Biomedical Materials Research - Part B Applied BiomaterialsJ. Biomed. Mater. Res. Part B Appl. Biomater., 2004)
The development of protein coating on 3D biodegradable scaffold based on electrostatic self-assembly (ESA) to promote osteoblast growth is reported. Poly (ethylenimine) (PEI) was employed to obtain a stable positively charged surface on poly(DL-lactide) (PDL-LA) substrate. An extracellular-matrix (ECM)-like biomacromolecule, gelatin, was chosen as the polyelectrolyte to deposit on the activated PDL-LA substrate via ESA technique. Osteoblast (MC3T3) was then cultured on unmodified and gelatin-modified PDL-LA scaffolds. Osteoblast testing regarding total intracellular protein content, total DNA content, cell activity, and cell morphology on the ECM-like multilayer-modified PDL-LA scaffold showed that osteoblast growth was promoted. It will be easy to replace the gelatin with osteoinductive proteins or other polyelectrolytes to promote specific osteoblast functions. In comparison with conventional coating methods, polyelectrolyte multilayers are easy and stable to prepare. They may be a good choice for the surface modification of complex biomedical devices, especially for the 3D tissue-engineering scaffold. These very flexible systems allow broad medical applications for drug delivery and tissue engineering. © 2004 Wiley Periodicals, Inc.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: JBMRGdoi: 10.1002/jbm.b.30080PubMed ID: 15368240Language of Original Document: EnglishCorrespondence Address: Ji, J.; Dept. of Poly. Sci. and Engineering, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: DNA, 9007-49-2; gelatin, 9000-70-8; polyethyleneimine, 74913-72-7; polylactide, 26680-10-4; DNA, 9007-49-2; Gelatin, 9000-70-8; poly(lactide), 26969-66-4; PolyestersReferences: Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681;Kim, B.S., Mooney, D.J., Development of biocompatible synthetic extracellular matrices for tissue engineering (1998) Trend Biotechnol, 16, pp. 224-230; Hunter, A., Archer, C.W., Walker, P.S., Blunn, G.W., Attachment and proliferation of osteoblasts and fibroblasts on biomaterials for orthopaedic use (1995) Biomaterials, 16, pp. 287-295; Goldstein, A.S., Juarez, T.M., Helmke, C.D., Gustin, M.C., Mikos, A.G., Effect of convection on osteoblastic cell growth and function in biodegradable polymer foam scaffolds (2001) Biomaterials, 22, pp. 1279-1288; Liao, H., Andersson, A.S., Sutherland, D., Petronis, S., Kasemo, B., Thomsen, P., Response of rat osteoblast-like cells to microstructured model surfaces in vitro (2003) Biomaterials, 24, pp. 649-654; Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., Ultrathin polymer coatings by complexation of polyelectrolytes at interfaces: Suitable materials, structure and properties (2000) Macromol Rapid Commun, 21, pp. 319-348; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Sano, M., Lvov, Y., Kunitake, T., Formation of ultrathin polymer layers on solid substrates by means of polymerization-induced epitaxy and alternate adsorption (1996) Ann Rev Mater Sci, 26, pp. 153-187; Laschewsky, A., Ultrathin polymer coatings by self-organization techniques. A critical comparison (1997) Eur Chem Chron, 2, pp. 13-24; Park, S.Y., Barrett, C.J., Rubner, M.F., Mayes, A.M., Anomalous adsorption of polyelectrolyte layers (2001) Macromolecules, 34, pp. 3384-3388; Sullivan, D.M., Bruening, M.L., Ultrathin, ion-selective polyimide membranes prepared from layered polyelectrolytes (2001) J Am Chem Soc, 123, pp. 11805-11806; Chluba, J., Voegel, J.C., Decher, G., Erbacher, P., Schaaf, P., Ogier, J., Peptide hormone covalently bound to polyelectrolytes and embedded into multilayer architectures conserving full biological activity (2001) Biomacromolecules, 2, pp. 800-805; Iler, R.K., Multilayers of colloidal particles (1966) J Colloid Interface Sci, 21, pp. 569-594; Decher, G., Hong, J.D., Buildup of ultrathin multilayer films by a self-assembly process: II. Consecutive adsorption of anionic and cationic bipolar amphiphiles and polyelectrolytes on charged surfaces (1991) Ber Bunsenges Phys Chem, 95, pp. 1430-1434; Decher, G., Fuzzy nanoassemblies: Toward layered polymeric multicomposites (1997) Science, 277, pp. 1232-1237; Lvov, Y., Decher, G., Moehwald, H., Assembly, structural characterization, and thermal behavior of layer-by-layer deposited ultrathin films of poly(vinyl sulfate) and poly(allylamine) (1993) Langmuir, 9, pp. 481-486; Lvov, Y., Haas, H., Decher, G., Moehwald, H., Mikhailov, A., Mtchedlishvily, B., Morgunova, E., Vainshtein, B.S., Successive deposition of alternate layers of polyelectrolytes and a charged virus (1994) Langmuir, 10, pp. 4232-4236; Kleinfeld, E.R., Ferguson, G.S., Stepwise formation of multilayered nanostructural films from macromolecular precursors (1994) Science, 265, pp. 370-373; Hong, D., Lowack, K., Schmitt, J., Decher, G., Layer-by-layer deposited multilayer assemblies of polyelectrolytes and proteins: From ultrathin films to protein arrays (1993) Progr Colloid Polym Sci, 93, pp. 98-102; Schmitt, J., Grunewald, T., Decher, G., Pershan, P.S., Krajer, K., Loesche, M., Internal structure of layer-by-layer adsorbed poly-electrolyte films: A neutron and X-ray reflectivity study (1993) Macromolecules, 26, pp. 7058-7063; Korneev, D., Lvov, Y., Decher, G., Schmitt, J., Yaradaikin, S., Neutron reflectivity analysis of self-assembled film super lattices with alternate layers of deuterated and hydrogenated polystyrenesulfonate and polyallylamine (1995) Physica B, 213-214, pp. 954-956; Zhu, H., Ji, J., Tan, Q., Barbosa, M.A., Shen, J., Surface engineering of poly (DL-lactide) via electrostatic self-assembly of extracellular matrix-like molecules (2003) Biomacromolecules, 4, pp. 378-386; Zhu, Y., Gao, C., He, T., Liu, X., Shen, J., Layer-by-layer assembly to modify poly(1-lactic acid) surface toward improving its cytocompatibility to human endothelial cells (2003) Biomacromolecules, 4, pp. 446-452; Miko, A.G., Sarakinos, G., Vacanti, J.P., Langer, R.S., Cima, L.G., Biocompatible polymer membranes and methods of preparation of three dimensional membrane structures. U. S. Patent No. 5,514378; 1996Instructions: BCA Protein Assay Reagent Kit 23227, , Pierce; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., Measurement of protein using bicinchoninic acid (1985) Anal Biochem, 150, pp. 76-85; (1998) Product Information: DNA Quantitation Kit Fluorescence Assay (DNA-QF), , SIGMA; West, D.C., Sattar, A., Kumar, S., A simplified in situ solubilization procedure for the determination of DNA and cell number in tissue cultured mammalian cells (1985) Anal Biochem, 147 (2), pp. 289-295; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Zund, G., Ye, Q., Hoerstrup, S.P., Schoeberlein, A., Schmid, A.C., Grunenfelder, J., Vogt, P., Turina, M., Tissue engineering in cardiovascular surgery: MTT, a rapid and reliable quantitative method to assess the optimal human cell seeding on polymeric meshes (1999) Eur J Cardio-thoracic Surg, 15, pp. 519-524
Keywords: 3T3 Cells; Absorbable Implants; Activation analysis; animal cell; Animals; article; Biodegradation; Biomedical engineering; cell activity; cell adhesion; Cell Division; cell growth; cell level; cell protein; cell structure; cell surface; Cell-material interactions; Cells; Coating techniques; DNA; DNA content; Drug products; Electrostatics; ethylene derivative; extracellular matrix; gelatin; Gelation; Growth (materials); Kinetics; macromolecule; materials testing; Mice; Microscopy, Confocal; mouse; nonhuman; osteoblast; Osteoblast growth; Osteoblast testing; Osteoblasts; polyelectrolyte; Polyelectrolytes; Polyesters; Polyethyleneimine; polylactide; polymer; protein assembly; Proteins; Surface modification; Tissue; Tissue engineering

Ribcage Boundary Delineation in Chest X-ray Images - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
We propose a method for segmenting the ribcage boundary of digital postero-anterior chest X-ray images. The segmentation is achieved by first defining image landmarks: the center of the ribcage and, using polar transformation from this point, two initial points belonging to the ribcage. A bank of Gabor filters (in analogy with the simple cells present in the human visual cortex) is used to obtain an orientation edges enhanced image. In this enhanced image, an edge following, starting from the landmarks previously determined, is performed for delineating the left and right sections of the ribcage. The complete segmentation is then accomplished by connecting these sections with the top section of the ribcage, obtained by means of spline interpolation. © Springer-Verlag 2004.
Keywords: Edge following; Gabor Filters; Polar image transform; Probabilistic genetic algorithm; Ribcage boundary segmentation

Scheduling parallel tasks on heterogeneous clusters - Barbosa, J.; Morais, C.; Monteiro, A.P. (Proceedings of the IASTED International Conference on Parallel and Distributed Computing and SystemsProc. IASTED INt. Conf. Parall. Distrib. Comput. Syst., 2004)
Parallel tasks, also called malleable tasks, are tasks that can be executed on any number of processors with its execution time being a function of the number of processors alloted to it. The scheduling of independent parallel tasks on homogeneous machines is a problem that has been extensively studied. For heterogeneous machines, with a diverse CPU capacity, new challenges arise, namely the selection of the set of CPUs that optimizes the processing time of a given task. This paper presents a methodology to determine the best allotment for each task that minimizes its processing time on a given heterogeneous machine. The aim is to improve the global processing time of a complex algorithm composed by several linear algebra kernels, by scheduling a number of parallel tasks in the heterogeneous machine. The results presented compare this approach to the simpler data parallel execution of each task on the heterogeneous cluster, i.e. executing one task at a time using the data parallel programming model.
Conference code: 64182Export Date: 21 November 2012Source: ScopusArt. No.: 439-085Language of Original Document: EnglishCorrespondence Address: Barbosa, J.; Faculdade de Engenharia, Universidade do Porto, Inst. de Engenharia Biomédica, Porto, Portugal; email: jbarbosa@fe.up.ptReferences: Amoura, A.K., Bampis, E., König, J.-C., Scheduling algorithms for parallel gaussian elimination with communication costs (1998) IEEE Transactions on Parallel and Distributed Systems, 9 (7), pp. 679-686. , July;Barbosa, J., Padilha, A.J., Algorithm-dependent method to determine the optimal number of computers in parallel virtual machines (1998) VECPAR'98, 1573. , Springer-Verlag LNCS; Barbosa, J., Tavares, J., Padilha, A., A group block distribution strategy for a heterogeneous ma chine (2002) Applied Informatics, pp. 378-383. , M. H. Hamza, editor. IASTED, ACTA Press, February; Barbosa, J., Tavares, J., Padilha, A.J., Linear algebra algorithms in a heterogeneous cluster of personal computers (2000) Proceedings of 9th Heterogeneous Computing Workshop, pp. 147-159. , IEEE CS Press, May; Berman, F., Wolski, R., Figueira, S., Schopf, J., Shao, G., Application-level scheduling on distributed heterogeneous networks (1996) Supercomputing, 96; Blazewicz, J., Dell'Olmo, P., Drozdowski, M., Maczka, P., Scheduling multiprocessor tasks on parallel processors with limited availability (2003) European Journal of Operational Research, (149), pp. 377-389; Boudet, V., Rastello, F., Robert, Y., A proposal for a heterogeneous cluster ScaLAPACK(dense linear solvers) (1999) Proceedings of PDPTA, , CSREA Press; Boulet, P., Dongarra, J., Rastello, F., Robert, Y., Vivien, F., Algorithmic issues on heterogeneous computing platforms (1999) Parallel Processing Letters, 9 (2), pp. 197-213; Choi, J., Dongarra, J., Ostrouchov, L.S., Petitet, A.P., Walker, D.W., Whaley, R.C., The design and implementation of the ScaLAPACK LU, QR, and CHOLESKY factorization routines (1996) Scientific Programming, 5, pp. 173-184; Geijn, R., Watts, J., Summa: Scalable universal matrix multiplication algorithm (1995) Technical Report, CS-95-286. , University of Tennessee, Knoxville; Hopper, E., Turton, B.C.H., An empirical investigation of meta-heuristic and heuristic algorithms for a 2d packing problem (2001) European Journal of Operational Research, 128, pp. 34-57; Jansen, K., Scheduling malleable parallel tasks: An asymptotic fully polynomial time approximation scheme (2004) Algorithmica, 39, pp. 59-81; Lepère, R., Mounié, G., Trystram, D., An approximation algorithm for scheduling trees of malleable tasks (2002) European Journal of Operational Research, (142), pp. 242-249; Oh-Heum, Chwa, K.-Y., Scheduling parallel tasks with individual deadlines (1999) Theoretical Computer Science, 215, pp. 209-223; Shirazi, B., Wang, M., Pathak, G., Analysis and evaluation of heuristic methods for static task scheduling (1990) Journal of Parallel and Distributing Computing, 10, pp. 222-232; Topcuoglu, H., Hariri, S., Wu, M.-Y., Performance-effective and low-complexity task scheduling for heterogeneous computing (2002) IEEE Transactions on Parallel and Distributed Systems, 13 (3), pp. 260-274. , March; Trystram, D., Scheduling parallel applications using malleable tasks on clusters (2001) 15th International Conference on Parallel and Distributed Processing Symposium Sponsors: Int. Association of Sci. and Technol. for Dev., IASTED; World Modelling and Simulation Forum (WMSF)
Keywords: Computational complexity; Computer programming; CPU capacity; Data handling; Directed acyclic graphs (DAG); Graph theory; Heterogeneous clusters; Linear algebra; Parallel algorithms; Parallel processing systems; Parallel/malleable tasks; Program processors; Scheduling

Study of a Silicate Cement for Dental Applications - Pereira, S.; Cavalheiro, J.; Branco, R.; Afonso, A.; Vasconcelos, M. (Key Engineering MaterialsKey Eng Mat, 2004)
Dental cements have a wide field of applications in clinical practice. The use as a base material is a very important one in dentistry. The aim of this study is to assess some relevant properties of a silicate cement (SC) developed for dental applications, comparing it with two other cements already commercialised, a zinc phosphate cement De Trey Zinc Cement Improved® (DT) and ProRootMTA®(MTA). Their compressive strength, dimensional changes and weight variation in water after setting, according to ISO standards were compared. The mean compressive strength of DT, MTA and SC were, respectively, 134MPa, 31MPa and 46MPa. There were no statistically significant differences for the three tested cements at the various time intervals, in respect to their weight variation or dimensional changes. However, there was a little loss of weight for DT (0.15%) and for MTA (3%) and a gain of 3% for the SC. Regarding the dimensional changes, all materials undergo little expansion, more significant in the MTA and in the SC samples of 2,07% and 0,4%, respectively. The new Silicate Cement, presented enough compressive strength, low weight variation, very small dimensional changes and good adaptation to the surface of dental cavity. For these reasons this new cement could be a valuable proposal as a base material for dental applications.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Pereira, S.; Fac. de Medicina Dentária, Universidade do Porto, R. Dr. Manuel Pereira da Silva, 4200-393 Porto, PortugalReferences: Craig, R.G., Rovers, J.M., (2002) Restorative Dental Materials. 9th Ed., pp. 593-627. , St Louis: Mosby;Gladwin, M., Bagby, M., (2000) Clinical Aspects of Dental Materials. First Edition, pp. 81-92. , Philadelphia: Lippincott Williams & Wilkins; Leinfelder, K.F., Changing Restorative Traditions: The Use of Bases and Liners (1994) JADA, 125, pp. 65-67; Macchi, R.L., (2000) Mat. Dentales. 3 a Ed., pp. 129-135. , Buenos Aires: Edit. Médica P.americana S.A; Wise, D.L., (1995) Encyclopedic Handbook of Biomaterials and Bioengineering, pp. 1398-1411. , New York: Marcel Dekver; Gordan, V.V., Mjör, I.A., Hucke, R.D., Smith, G.E., Effect of Different Liner Treatments on Postoperative Sensivity of Amalgam Restorations (1999) Quintessence Int, 30, pp. 55-59; Me, M., Nakai, H., Effect of Immersion in Water on Linear Expansion and Strength of Three Base/Liner Materials (1995) Dent Mater, 14, pp. 70-77; Leevailoj, C., Cochran, M.A., Matis, B.A., Moore, B.K., Platt, J.A., Microleakage of Posterior Packable Resin Composites with and without Flowable Liners (2001) Oper Dent, 26, pp. 302-307; Weiner, R.S., Weiner, L.K., Kugel, G., Teaching the Use of Bases and Liners: A Survey of the North American Dental Schools (1996) JADA, 127, pp. 1640-1645; Pereira, S., Branco, R., Cavalheiro, J., Afonso, A., Vasconcelos, M., (2003) Sealing Ability of a New Dental Base Material, , Bioeng; (1991) Specification for Dental Water-based Cements, , ISO 9917 (F)
Keywords: Biocompatibility; Body fluids; Ceramic materials; ceramics; Compressive Strength; Dental cement; Dental cements; Dental prostheses; Dimensional stability; Precipitation (chemical); Scanning electron microscopy; Silicate cements; Silicates; Stainless steel; Weight variation

Ultrastructural comparison of dissolution and apatite precipitation on hydroxyapatite and silicon-substituted hydroxyapatite in vitro and in vivo - Porter, A.E.; Botelho, C.M.; Lopes, M.A.; Santos, J.D.; Best, S.M.; Bonfield, W. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2004)
Recent histological studies have demonstrated that the substitution of silicate ions into hydroxyapatite (HA) significantly increases the rate of bone apposition to HA implants. The enhanced bioactivity of silicon-substituted HA (Si-HA) over pure HA has been attributed to the effect of silicate ions in accelerating dissolution. In the present study, high-resolution transmission electron microscopy (HR-TEM) was employed to compare dissolution of HA and Si-HA in an acellular simulated body fluid (SBF) to dissolution in an in vivo model. HR-TEM observations confirmed a difference in morphology of apatite precipitates in vivo and in SBF: apatite deposits were platelike in vivo and nodular in SBF. Compositional mapping suggested that preferential dissolution of silicon from the implant promotes the nucleation of carbonate apatite around the implant. The in vivo findings illustrated an absence of dissolution at the bone-HA or Si-HA interface, whereas dissolution was extensive from within the implant. The amount of dissolution in acellular SBF was similar to dissolution from within the implant, although the site at which the dissolution nucleates was different: dissolution predominates at the crystallite surfaces in SBF, whereas grain boundary dissolution predominates in vivo. These findings suggest that proteins in the in vivo milieu modify the processes of dissolution from the implant. © 2004 Wiley Periodicals, Inc.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: JBMRCPubMed ID: 15162409Language of Original Document: EnglishCorrespondence Address: Porter, A.E.; Dept. of Mat. Science and Metallurgy, University of Cambridge, Pembroke Street, Cambridge, CB2 3QZ, United Kingdom; email: aep30@cam.ac.ukChemicals/CAS: apatite, 64476-38-6; carbonic acid, 3812-32-6, 463-79-6; hydroxyapatite, 1306-06-5, 51198-94-8; silicon, 7440-21-3; Biocompatible Materials; Durapatite, 1306-06-5; Silicon, 7440-21-3References: Porter, A.E., Best, S.M., Bonfield, W., Ultrastructural comparison of hydroxyapatite and silicon-substituted hydroxyapatite for biomedical applications (2003) J Biomed Mater Res, 68 A, pp. 133-141;Patel, N., Gibson, I.R., Hing, K.A., Best, S.M., Revell, P.A., Bonfield, W., A comparative study on the in vivo behaviour of hydroxyapatite and silicon substituted hydroxyapatite granules (2002) J Mater Sci Mater Med, 13, pp. 1199-1206; Porter, A.E., Patel, N., Skepper, J.N.S., Best, S.M., Bonfield, W., Comparison of in vivo dissolution processes in hydroxyapatite and silicon-hydroxyapatite bioceramics (2003) Biomaterials, 24, pp. 4609-4620; Weng, J., Liu, Q., Wolke, J.G.C., Zhang, X., De Groot, K., Formation and characteristics of the apatite layer on plasma-sprayed hydroxyapatite coatings in simulated body fluid (1995) Biomaterials, 18, pp. 1027-1035; Doi, Y., Shibutani, T., Moriwake, Y., Kajimoto, T., Iwayama, Y., Sintered carbonate apatites as bioresorbable bone substitutes (1997) J Biomed Mater Res, 39, pp. 603-610; Schepers, E., Declercq, M., Ducheyne, P., Kempeneers, R., Bioactive glass particulate material as a filler for bone lesions (1991) J Oral Rehab, 18, pp. 439-452; Ducheyne, P., Qiu, Q., Bioactive ceramics: The effect of surface reactivity on bone formation and bone cell function (1999) Biomaterials, 20, pp. 2287-2303; Ducheyne, P., Radin, S., King, L., The effect of calcium-phosphate ceramic composition and structure on in vitro behaviour. I. Dissolution (1993) J Biomed Mater Res, 27, pp. 25-34; Kukubo, T., Kushitani, H., Sakka, S., Solutions able to reproduce in vivo surface-structure changes in bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 721-734; Radin, S.R., Ducheyne, P., The effect of calcium phosphate ceramic composition and structure on in vitro behavior. II. Precipitation (1993) J Biomed Mater Res, 27, pp. 35-45; Gibson, I.R., Hing, K.A., Best, S.M., Bonfield, W., Enhanced in vitro cell activity and surface apatite layer formation on novel silicon-substituted hydroxyapatites (1999) 12th International Symposium on Ceramics in Medicine, pp. 191-194. , Ohgushi H, Hastings GW, Yoshikawa T, editors. Nara, Japan. World Scientific; Fujibayashi, S., Neo, M., Kim, H.-M., Kokubo, T., Nakamura, T., A comparative study between in vivo bone ingrowth and in vitro apatite formation on Na 2-CaO-SiO 2 glasses (2003) Biomaterials, 24, pp. 1349-1356; Porter, A.E., Patel, N., Skepper, J.N., Best, S.M., Bonfield, W., Effect of sintered silicate-substituted hydroxyapatite on remodelling processes at the bone-implant interface (2003) Biomaterials, 25, pp. 3303-3314; Leng, Y., Chen, J., Qu, S., TEM study of calcium phosphate precipitation on HA/TCP ceramics (2003) Biomaterials, 24, pp. 2125-2131; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 28, p. 809; Gibson, I.R., Best, S.M., Bonfield, W., Chemical characterization of silicon-substituted hydroxyapatite (1999) J Biomed Mater Res, 44, pp. 422-428; Rey, C., Calcium phosphates for medical applications (1998) Calcium Phosphates in Biological and Industrial Systems, pp. 217-251. , Amjad Z, editor. Kluwer Academic: Boston; Tanizawa, Y., Suzuki, T., Effects of silica ions on the formation and transformation of calcium phosphates in neutral aqueous solutions (1995) J Chem Soc Faraday Trans, 91, pp. 3499-3503; Damen, J.J.M., Ten Cate, J.M., Silica-induced precipitation of calcium phosphate in the presence of inhibitors of hydroxyapatite formation (1992) J Dent Res, 71, pp. 453-457; Botelho, C.M., Lopes, M.A., Gibson, I.R., Best, S.M., Santos, J.D., Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy (XPS) (2002) J Mater Sci Mater Med, 13, pp. 1123-1127; Carlisle, E.M., Silicon (1975) Nutr Rev, 33, pp. 257-260; Termine, J.D., Eanes, E.D., Conn, K.M., Phosphoprotein modulation of apatite crystallization (1980) Calcif Tissue Int, 31, pp. 247-251; Combes, C., Rey, C., Adsorption of proteins and calcium phosphate materials bioactivity (2002) Biomaterials, 23, pp. 2817-2823; Horbett, T.A., Proteins at interfaces - An overview (1995) ACS Symp Ser, pp. 602-623
Keywords: Apatite; article; Bioactivity; Biocompatible Materials; body fluid; carbonic acid; comparative study; Composition; Dissolution; Durapatite; histology; hydroxyapatite; implant; Implants (surgical); in vitro study; in vivo study; Interfaces (materials); Microscopy, Electron; Microscopy, Electron, Scanning; morphology; precipitation; Precipitation (chemical); Silicon; Simulated body fluid; Simulated body fluids (SBF); simulation; transmission electron microscopy; ultrastructure

The Valences of Egg White for Designing Smart Porous Bloceramics: As Foaming and Consolidation Agent - Lemos, A.F.; Ferreira, J.M.F. (Key Engineering MaterialsKey Eng Mat, 2004)
Porous hydroxyapatite bioceramics were developed by a new direct consolidation method based on the foaming capability of egg white and on its gelling properties on heating, thus acting both as pore former and consolidator agent. The bubble forming capability of fresh egg white, due to the presence of a globular protein - albumen, allows the formation of a stable foam when added to a ceramic suspension. Adding a sufficient amount of the globular protein to the suspension revealed to be crucial to control either the pore volume fraction as well as the gelling behaviour and the rigidity of the green bodies. This consolidation method can be performed in nonporous moulds, enabling materials with controlled porosity to be obtained by varying the egg white content in the slip composition. After drying, burnout and sintering, materials with ultimate porosities close to 75 % were obtained.
Conference code: 62053Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Lemos, A.F.; Ceramic Engineering Department, Campus de Santiago, University of Aveiro, 3810-193 Aveiro, Portugal; email: ilemos@cv.ua.ptReferences: De Groot, K., (1980) Biomaterials, 1, p. 47;Ohgushi, H., Okumura, M., Yoshikawa, T., Inoue, K., Senpuku, N., Tamai, S., Shors, E.C., (1992) J. Biomed. Mater. Res., 26, p. 885; Omatete, O., Janney, M.A., Strehlow, R.A., (1991) Am. Ceram Soc.Bull., 70, p. 1641; Kosmac, T., Novak, S., Sajko, M., (1995) Fourth Euro Ceramics Vol. 1, Basic Science: Developments, 1. , ed. C. Galassi. Gruppo Editoriale Faenza Editrice S.p.a., Italy; Graule, T.J., Baader, F.H., Gauckler, L.J., (1994) Cfi/Ber. DKH., 71, p. 317; Novich, B.E., Sundback, C.A., Adams, R.W., (1992) Ceramic Transactions, 26. , ed. M. J. Cima. American Ceramic Society, USA; Lycfeldt, O., Ferreira, J.M.F., (1998) J. Eur. Ceram. Soc., 18, p. 131; Rives, R.D., U. S. Patent 4113480 (1976)Lycfeldt, O., Brandt, J., Lesca, S., (2000) J. Eur. Ceram. Soc., 20 (14-15), p. 2551; Olhero, S.M., Tarì, G., Coimbra, M.A., Ferreira, J.M.F., (2000) J. Europ. Ceram. Soc., 20 (4), p. 423; Dhara, S., Bhargava, P., (2001) J. Am. Ceram. Soc., 84 (12), p. 3048; Janney, M.A., Omatete, O., Walls, C., Nunn, S., Ogle, R., Westmoreland, G., (1998) J. Am. Ceram. Soc., 81 (3), p. 581; Lumry, R., Eyring, H., (1954) J. Phys. Chem., 58, p. 110; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., (2003) Advanced Materials Forum
Keywords: Bioceramics; Biodegradation; Bone-grafting; Ceramic materials; Consolidation technique; Consolidation techniques; Egg-white; heating; hydroxyapatite; morphology; Pore size; porosity; Porous ceramics; Porous materials; Proteins; Slurries; Solidification

XRD and FT-IR characterisation of hydroxyapatite sputtered films on titanium - Silva, R.A.; Sousa, M.; Monteiro, F.J.; Barrai, R.; Lopes, M.A. (Transactions - 7th World Biomaterials CongressTrans. World Biomater. Congr., 2004)
XRD and FT-IR were used to characterize hydroxyapatite (HA) films, which were prepared using rf sputtering. The morphology of the sample films was analyzed using SEM. From the FT-IR spectrum, sputtered HA films showed structural changes, namely the decrease of the strength of the liberational mode of OH group, indicating the presence of a poorly crystalline phase. XRD results of films obtained at 500 W and 400 W showed that the crystallinity of the 500 W 4h e 2h samples was low, just showing a very incipient degree of crystalline structural structural arrangement, while in the 400 W-4h and 2h samples there was no crystalline structure, with only a slight diffraction of the 002 and 301 HA planes.
Conference code: 64310Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Silva, R.A.; Inst. Sup. de Engenharia do Porto, Rua Dr.Antonio Bernardino A., 431, 4200- 072 Porto, Portugal; email: ras@isep.ipp.ptReferences: Wolke, J.G.C., (1998) J.Biomed. Mat. Res, 39, pp. 524-530;Silva, R.A., Proceedings of Bioceramics 16, , to be published
Keywords: Absorption bands; Adsorption; Bioactive films; Biomaterials; Bone; crystal structure; Crystallinity; Deposition; Fourier transform infrared spectroscopy; hydroxyapatite; Hydroxyapatite films; morphology; Scanning electron microscopy; Sintering; Sputtering; Surface topography; Thin films; Titanium; X ray diffraction analysis

Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces - Barbosa, J.N.; Barbosa, M.A.; Água, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2003)
The adhesion of human leukocytes to self-assembled monolayers of well-defined surface chemistry was investigated in vitro. Polymorphonuclear (PMN) and mononuclear leukocytes were isolated from human blood by centrifugation techniques. The effect on adhesion of cell activation produced by pre-incubation of leukocytes with phytohemagglutinin (PHA) and phorbol 12-myristate 13-acetate (PMA) was also studied. Gold substrates were modified by treatment with alkanethiols with three different terminal chemical groups: COOH, OH, and CH 3. After incubation with the two subpopulations of leukocytes, the monolayers were washed, treated with fixative, stained with a Giemsa method, and observed by light microscopy to quantify the number of attached leukocytes. Comparative quantification of the density of leukocyte adhesion to the three types of self-assembled monolayers was determined. The hydrophobic surface expressing CH 3 was found to be the one that induced the highest adhesion density of leukocytes, both of PMN and mononuclear cells. In vitro activation of both mononuclear and PMN leukocytes further increased cell adhesion to the chemically defined monolayers that were used. This enhancement was higher for PHA-activated than for PMA-stimulated mononuclear cells, whereas PMA treatment of neutrophils resulted in a higher rate of adhesion of these cells than PHA stimulation. © 2003 Wiley Periodicals, Inc.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusCODEN: JBMRCLanguage of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB-Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; hydroxide, 14280-30-9; methane, 74-82-8; phorbol 12 acetate 13 myristate, 31365-46-5; phytohemagglutinin, 9008-97-3; phorbol 13 acetate 12 myristate, 16561-29-8; Biocompatible Materials; Gold, 7440-57-5; Phytohemagglutinins; Tetradecanoylphorbol Acetate, 16561-29-8References: Jones, D.A., Smith, C.W., McIntire, L.V., Leucocyte adhesion under flow conditions: Principles importante in tissue engineering (1996) Biomaterials, 17, pp. 337-347;Marchant, R.E., Cell adhesion and interactions with biomaterials (1984) J Adhes, 20, pp. 211-225; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Brunstedt, M.R., Anderson, J.M., Spilizewski, K.L., Marchant, R.E., Hiltner, A., In vivo leucocyte interactions on Pellethane surfaces (1990) Biomaterials, 11, pp. 370-378; Kao, W.J., Evaluation of leukocyte adhesion on polyurethanes: The effects of shear stress and blood proteins (2000) Biomaterials, 21, pp. 2295-2303; Lim, F., Cooper, S.L., Effect of sulphonate incorporation on in vitro leucocyte adhesion to polyuretanes (1995) Biomaterials, 16, pp. 457-466; Tomczok, J., Sliwa-Tomczok, W., Klein, C.L., Van Kooten, T.G., Kirkpatrick, C.J., Biomaterial-induced alterations of human neutrophils under fluid shear stress: Scanning electron microscopical study in vitro (1996) Biomaterials, 17, pp. 1359-1367; Yun, J.K., DeFife, K., Colton, E., Stack, S., Azeez, A., Cahalan, L., Verhoeven, M., Anderson, J.M., Human monocyte/macrophage adhesion and cytokine production on surface-modified poly(tetrafluoroethylene/hexafluoropropylene) polymers with and without protein preadsorption (1995) J Biomed Mater Res, 29, pp. 257-268; Mrksich, M., Whitesides, G.M., Interactions of SAMs with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrkisich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Kane, R.S., Takayama, S., Ostuni, E., Ingber, D.E., Whitesides, G.M., Patterning proteins and cells using soft lithography (1999) Biomaterials, 20, pp. 2363-2376; Mrksich, M., Using self-assembled monolayers to understand the biomaterials interface (1997) Curr Opin Colloid Int Sci, 2, pp. 83-88; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Prime, K.L., Whitesides, G.M., Self assembled organic monolayers model systems for studying the adsorption of proteins at surfaces (1991) Science, 252, pp. 1164-1167; Lopez, G.P., Albers, M.W., Schreiber, S.L., Carroll, R., Peralta, E., Whitesides, G.M., Convenient methods for patterning the adhesion of mammalian cells to surfaces using self-assembled monolayers of alkane thiolates on gold (1993) J Am Chem Soc, 115, pp. 5877-5878; Shinghvi, R., Kumar, A., Lopez, G.P., Stephanopoulos, G.N., Wang, D.I.C., Whitesides, G.M., Ingber, D.E., Engineering cell shape and function (1994) Science, 264, pp. 696-698; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiencies for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkane thiols on gold surfaces (1997) Biomaterials, 18, pp. 1059-1068; Baker, L.C., Davis, W.C., Autieri, J., Watach, M.J., Yamazaki, K., Litwak, P., Wagner, W.R., Flow cytometric assays to detect platelet activation and aggregation in device-implanted calves (1998) J Biomed Mater Res, 41, pp. 312-321; English, D., Andersen, B.R., Single-step separation of red blood cells. Granulocytes and mononuclear leukocytes on discontinuous density gradient of ficoll-hypaque (1974) J Immunol Methods, 5, pp. 249-253; Nygren, H., Hrustic, E., Karlsson, C., Öster, L., Respiratory burst response of peritoneal leukocytes adhering to titanium and stainless steel (2001) J Biomed Mater Res, 57, pp. 238-247; Gorbet, M.B., Yeo, E.L., Sefton, M.V., Flow cytometric study of in vitro neutrophil activation by biomaterials (1999) J Biomed Mater Res, 44, pp. 289-297; Källtrorp, M., Askendal, A., Thompsen, P., Tengvall, P., Inflammatory cell recruitment, distribution, and chemiluminescence response at IgG precoated- and thiol functionalized gold surfaces (1999) J Biomed Mater Res, 47, pp. 251-259; Mahiout, A., Courtney, J.M., Effect of dialyser membranes on extracellular and intracellular granulocyte and monocyte activation in ex vivo pyrogen-free conditions (1994) Biomaterials, 15, pp. 969-980; Davis, R.G., Goodman, S.B., Smith, R.L., Lerman, J.A., Williams III, R.J., The effects of bone cement powder on human adherent monocytes/ macrophages in vitro (1993) J Biomed Mater Res, 27, pp. 1039-1046; Gery, I., Gerhon, R.K., Waskman, B., Potentiation of the T lymphocyte response to mitogens. I. The responding cell (1972) J Exp Med, 136, pp. 128-134; Peters, S.P., Cerasoli Jr., F., Albertine, K.H., Gee, M.H., Berd, D., Ishihara, Y., "Autoregulation" of human neutrophil activation in vitro: Regulation of phorbol myristate acetate-induced neutrophil activation by cell density (1990) J Leukocyte Biol, 47, pp. 457-474; Esaguy, N., Águas, A.P., Vilanova, M., Silva, M.T., Activation of human neutrophils by phorbol ester decreases the cytoplasm compactness and the lactoferrin content of the granulocytes (1991) J Leukocyte Biol, 50, pp. 444-452; Collins, D.P., Cytokine and cytokine receptor expression as a biological indicator of immune activation: Important considerations in the development of in vitro model systems (2000) J Immunol Methods, 243, pp. 125-145; Ruoslahti, E., Integrin signaling and matrix assembly (1996) Tumor Biol, 17, pp. 117-128; Aoudjit, F., Vuori, K., Engagement of the α2β1 integrin inhibits Fas ligand expression and activation-induced cell death in T cells in a focal adhesion kinase-dependent manner (2000) Blood, 95, pp. 2044-2051; Lehr, H.A., Krombach, F., Munzing, S., Bodlaj, R., Glaubitt, S.I., Seiffge, D., Hubner, C., Messmer, K., In vitro effects of oxidized low density lipoprotein on CD11b/CD18 and L-selectin presentation on neutrophils and monocytes with relevance for the in vivo situation (1995) Am J Pathol, 146, pp. 218-227; Kansas, G.S., Tedder, T.F., Transmembrane signals generated through MHC class II, CD19, CD20, CD39, and CD40 antigens induce LFA-1-dependent adhesion in human B cells through a tyrosine kinase-dependent pathway (1991) J Immunol, 147, pp. 4094-4102; Damle, N.K., Eberhardt, C., Van Der Vieren, M., Direct interactions with primed CD4+ CD45R0+ memory T lymphocytes induces expression of endothelial leukocyte adhesion molecule-1 and vascular cell adhesion molecule-1 on the surface of vascular endothelial cells (1991) Eur J Immunol, 21, pp. 2915-2923; Murata, S., Tanaka, T., Miysaka, M., Lymphocyte binding to MAd-CAM-1 via α4β7 integrin activates a signal transduction pathway involving tyrosine phosphorylation of paxillin and p105 Cas-L (2002) Immunol Lett, 81, pp. 223-228; Roth, S.J., Carr, M.W., Rose, S.S., Springer, T.A., Characterization of transendothelial chemotaxis of T lymphocytes (1995) J Immunol Methods, 188, pp. 97-116; Aziz, K.E., Wakefield, D., In vivo and in vitro expression of adhesion molecules by peripheral blood lymphocytes from patients with primary Sjogren's syndrome: Culture-associated enhancement of LECAM-1 and CD4 (1995) Rheumatol Int, 15, pp. 69-74; Tengvall, P., Lundstrom, I., Liedberg, B., Protein adsorption studies on model organic surfaces: An ellipsometric and infrared spectroscopic approach (1998) Biomaterials, 19, pp. 407-422; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalised self-assembled monolayers of alkanethiols on gold (1997) Langmuir, 13, pp. 3404-3413; Tsai, M., Lin, J., Surface characterization and platelet adhesion studies of self-assembled monolayer with phosphonate ester and phosphonic acid functionalities (2001) J Biomed Mater Res, 55, pp. 554-565; Franco, M., Nealy, P.F., Campbell, S., Teixeira, A.I., Murphy, C.J., Adhesion and proliferation of corneal epithelial cells on self-assembled monolayers (2000) J Biomed Mater Res, 52, pp. 261-269; Scotchford, C.A., Gilmore, C.P., Cooper, E., Leggett, G.J., Downes, S., Protein adsorption and human osteoblast-like cell attachment and growth on alkylthiol on gold self-assembled monolayers (2002) J Biomed Mater Res, 59, pp. 84-99; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the non-specific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interface Sci, 185, pp. 94-103
Keywords: alkane derivative; article; Biocompatible Materials; biomaterial; Biomaterials; Blood; carboxyl group; cell adhesion; cell interaction; cell isolation; cell subpopulation; cell surface; Cell-surface interactions; Cells; Centrifugation; controlled study; drug effect; Giemsa stain; gold; human; human cell; Humans; hydrophobicity; hydroxide; in vitro study; Incubation; lectin; Lectins; leukocyte; Leukocyte activation; leukocyte adherence; Leukocyte adhesion; Leukocytes; Leukocytes, Mononuclear; materials testing; methane; microscopy; Monolayers; mononuclear cell; neutrophil; Neutrophils; Optical microscopy; phorbol 12 acetate 13 myristate; phorbol 13 acetate 12 myristate; physiology; phytohemagglutinin; Phytohemagglutinins; polymorphonuclear cell; Self-assembled monolayers; Surface Properties; surface property; Tetradecanoylphorbol Acetate; thiolacid

Albumin adsorption on alkanethiols self-assembled monolayers on gold electrodes studied by chronopotentiometry - Martins, M.C.L.; Fonseca, C.; Barbosa, M.A.; Ratner, B.D. (BiomaterialsBiomaterials, 2003)
Chronopotentiometry was used to study the adsorption of human serum albumin (HSA) to self-assembled monolayers with the following terminal functional groups: CH 3, COOH and OH. Surfaces were characterized by X-ray photoelectron spectroscopy, water contact angle measurements and cyclic voltammetry. HSA coverage of the different SAMs was investigated by chronopotentiometry and the total amount of adsorbed protein was determined using radiolabelled albumin. Both techniques have demonstrated that HSA adsorption to the different SAM-modified electrodes increases in the following order: OH<COOH<CH 3-terminated SAMs. A good correlation between coverage and total amount of HSA adsorbed was observed for long adsorption times (900s). © 2003 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00244-8PubMed ID: 12818541Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB - Inst. de Engenharia Biomed., Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; thiol derivative, 13940-21-1; water, 7732-18-5; Albumins; Alkanes; Biocompatible Materials; Gold, 7440-57-5; Serum Albumin; Sulfhydryl CompoundsReferences: Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, J.L., (1996) Biomaterials science - an introduction to materials in medicine, , San Diego, CA, USA: Academic Press;Nakanishi, K., Sakiyama, T., Imamura, K., On the adsorption of proteins on solid surfaces, a common but very complicated phenomenon (2001) J Biosci Bioeng, 91, pp. 233-244; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers to understand the interactions of man-made surfaces with proteins and cells (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-78; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120, pp. 3464-3473; Taborelli, M., Eng, L., Descouts, P., Ranieri, J.P., Bellamkonda, R., Aebisher, P., Bovine serum albumin conformation on methyl and amine functionalized surfaces compared by scanning force microscopy (1995) J Biomed Mater Res, 29, pp. 707-714; Silin, V., Weetall, H., Vanderah, D., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interface Sci, 185, pp. 94-103; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Wadu-Mesthrige, K., Amro, N.A., Liu, G., Immobilization of proteins on self-assembled monolayers (2000) Scanning, 22, pp. 380-388; Takahara, A., Hara, Y., Kojio, K., Kajiyama, T., Plasma protein adsorption behaviour onto the surface of phase-separated organosilane monolayers on the basis of scanning force microscopy (2002) Colloids Surf B: Biointerfaces, 23, pp. 141-152; Kalltorp, M., Carlén, A., Thomsen, P., Olsson, J., Tengvall, P., Analysis of rat plasma proteins desorbed from gold and methyl- and hydroxyl-terminated alkane thiols on gold surfaces (2000) J Mater Sci: Mater Med, 11, pp. 191-199; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Endothelial cell growth and protein adsorption on terminal functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Ulman, A., (1991) An introduction to ultrathin organic films: From Langmuir-Blodgett to self-assembled, , San Diego, CA, USA: Academic Press; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionlity (2000) J Biomed Mater Res, 51, pp. 413-423; Mirsky, V.M., Riepl, M., Wolfbeis, O.S., Capacitive monitoring of protein immobilization and antigen/antibody reactions on monomolecular alkylthiol films on gold electrodes (1997) Biosensors Bioelectron, 12, pp. 977-989; Viana, A.S., Jones, A.H., Abrantes, L.M., Kalaji, M., Redox induced orientational changes in a series of short chain ferrocenyl alkyl thiols self-assembled on gold(1 1 1) electrodes (2001) J Electroanal Chem, 500, pp. 290-298; Kondo, T., Okamura, M., Uosaki, K., Anion effect on the electrochemical characteristics of a gold electrode modified with a self-assembled monolayer of ferrocenylhexanethiol in aqueous and dichlomethane solutions (2001) J Organometal Chem, 637-639, pp. 841-844; Dong, S., Li, J., Self-assembled monolayers of thiols on gold electrodes for bioelectrochemistry and biosensors (1997) Bioelectrochem Bioenergetics, 42, pp. 7-14; Gooding, J.J., Hibbert, D.B., The application of alkanethiol self-assembled monolayers to enzyme electrodes (1999) Trends Anal Chem, 18, pp. 525-533; Spangler, B.D., Tyler, B.J., Capture agents for quartz crystal microbalance-continuous flow biosensor: Functionalized self-assembled monolayers on gold (1999) Anal Chem Acta, 399, pp. 51-62; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Tengvall, P., Lundstrom, I., Liedberg, B., Protein adsorption studies on model organic surfaces: An ellipsometric and infrared spectroscopic approach (1998) Biomaterials, 19, pp. 407-422; Shen, D., Huang, M., Chow, L., Yang, M., Kinetic profile of the adsorption and conformational change of lysozyme on self-assembled monolayers as revealed by quartz crystal resonator (2001) Sensor Actuators B, 77, pp. 664-670; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, 2, pp. 183-214. , Williams D.F. Harcover: CRC Press; Du, Y.J., Cornelius, R.M., Brash, J.L., Measurement of protein adsorption to gold surface by radioiodination methods: Suppression of free iodide sorption (2000) Colloid Surf B, 17, pp. 59-67; Smith, P.K., Krohn, R.I., Hermanson, G.T., Mallia, A.K., Gartner, F.H., Provenzano, M.D., Fujimoto, E.K., Klenk, D.C., Measurement of protein using bicinchoninic acid (1985) Anal Biochem, 150, pp. 756-785; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125. A Guide to Radioiodination Techniques, p. 64. , Amersham Life Science. Little Chalfort, UK: Amersham International plc; Bain, C.D., Evall, J., Whitesides, G.M., Formation of monolayer coadsorption of thiols on gold: Variation in the head group, tail group and solvent (1989) J Am Chem Soc, 111, pp. 7155-7164; Castner, D.G., Hinds, K., Grainger, D.W., X-ray photoelectron spectroscopy sulfur 2p study of organic thiol and disulfide binding interactions with gold surfaces (1996) Langmuir, 12, pp. 5083-5086; Keller, H., Schrepp, W., Fuchs, H., Self-assembled organic films on gold and silver (1992) Thin Solid Films, 210-211, pp. 799-802; Chidsey, C.E.D., Loiacono, D.N., Chemical functionality in self-assembled monolayers: Structural and electrochemical properties (1990) Langmuir, 6, pp. 682-691; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., Spontaneously organized molecular assemblies. 4. Structural characterization of n-alkyl thiol monolayers on gold by optical ellipsometry, infrared spectroscopy and electrochemistry (1987) J Am Chem Soc, 109, pp. 3559-3568; Miller, C., Cuendet, P., Gratzel, M., Adsorbed ω-hydroxy thiol monolayers on gold electrodes: Evidence for electron tunneling to redox species in solution (1991) J Phys Chem, 95, pp. 877-886; Krysinski, P., Brzostowska-Smolska, M., Capacitance characteristics of self-assembled monolayers on gold electrode (1998) Bioelectrochem Bioenergetics, 44, pp. 163-168; Guo, B., Anzai, J., OSA, T., Adsorption behaviour of serum albumin on electrodes surfaces and the effects of electrode potential (1996) Chem Pharm Bull, 44, pp. 800-803; Dent, A.H., Aslam, M., Other categories of protein coupling (1998) Bioconjugation, protein coupling techniques for the biomedical sciences, pp. 504-569. , M. Aslam, & A.H. Dent. London: Macmillan; Seigal, R.R., Harder, P., Dahint, R., Grunze, M., On-line detection of nonspecific protein adsorption at artificial surfaces (1997) Anal Chem, 69, pp. 3321-3328; Norde, W., Giacomelli, C.E., BSA structural changes during homomolecular exchange between the adsorbed and the dissolved states (2000) J Biotechnol, 79, pp. 259-268; Peters T., Jr., (1996) All about albumin: Biochemistry, genetics, and medical applications, , San Diego, CA, USA: Academic Press; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isoterms, competitivity, desorption and exchange of albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333
Keywords: Adsorption; Albumin; Albumin adsorption; Albumins; alkane; Alkanes; article; Biocompatible Materials; biomaterial; Biomaterials; carboxyl group; Chemical modification; Chronopotentiometry; Contact angle; correlation analysis; cyclic potentiometry; Cyclic voltammetry; electrochemistry; electrode; Electron Probe Microanalysis; Functional groups; gold; Humans; hydroxyl group; isotope labeling; methyl group; Monolayers; potentiometry; priority journal; protein analysis; Self assembly; Self-assembled monolayers; Serum Albumin; Sulfhydryl Compounds; Surface modification; Surface Properties; surface property; temperature; thiol derivative; Time Factors; Water; X ray photoelectron spectroscopy

Albumin adsorption on Cibacron Blue F3G-A immobilized onto oligo(ethylene glycol)-terminated self-assembled monolayers - Martins, Ma.C.L.; Naeemi, E.; Ratner, B.D.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2003)
Self-assembled monolayers can be tailored with specific ligands to a certain protein and at the same time prevent the non-specific adsorption of other proteins. Cibacron Blue F3G-A (CB-thiol) was successfully immobilized onto tetra(ethylene glycol)-terminated alkanethiol (CB-thiol). The affinity of human serum albumin (HSA) to immobilized Cibacron Blue F3G-A was studied using mixed thiolate self-assembled monolayers on gold with different n-alkyl chain lengths and functional terminal groups (CH 3-; OH- and tetra(ethylene glycol)). Surfaces were characterized using X-ray photoelectron spectroscopy and water contact angle measurements. Albumin adsorption and exchangeability of the adsorbed albumin molecules with other albumin molecules in solution were evaluated using 125I-radiolabeled HSA. Competitive adsorption between albumin and fibrinogen to the different self-assembled monolayers (SAMs) was also investigated. Results showed that the incorporation of CB-thiol on the monolayers does not increase the HSA adsorption and reversibility on the SAMs. However, although specific adsorption of HSA to the immobilized Cibacron Blue F3G-A was not demonstrated, the presence of CB-thiol decreases the affinity of fibrinogen to the OH-terminated SAMs. © 2003 Kluwer Academic Publishers.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1026394431100Language of Original Document: EnglishCorrespondence Address: Martins, Ma.C.L.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: cibacron blue f3ga, 12236-82-7, 53127-08-5; ethylene glycol, 107-21-1; fibrinogen, 9001-32-5; gold, 7440-57-5; human serum albumin, 9048-49-1; iodine 125, 14158-31-7, 22822-81-7; macrogol, 25322-68-3; thiol derivative, 13940-21-1; water, 7732-18-5References: Ratner, B.D., (1996) J. Mol. Recognit., 9, p. 617;Kottke-Marchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., (1998) Biomaterials, 10, p. 147; Dequeiroz, A.A.A., Barrak, E.R., Gil, H.A.C., Higa, O.Z., (1997) J. Biomater. Sci. Polym. Ed., 8, p. 667; Kamath, K.R., Park, K., (1994) J. Appl. Biomater., 5, p. 163; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., (1981) Trans. Am. Soc. Artif. Intern. Organs, 27, p. 499; Ji, J., Feng, L., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Keogh, J.R., Eaton, J.W., (1994) J. Lab. Clin. Med., 121, p. 537; Wang, D., Chen, B., Ji, J., Feng, L., (2002) Bioconjugate Chem., 13, p. 792; Ji, J., Barbosa, M.A., Feng, L., Shen, J., (2002) J. Mat. Sci. Mat. Med., 13, p. 677; Mcfarland, C.D., Jenkins, M., Griesser, H.J., Chatelier, R.C., Steele, J.G., Underwood, P.A., (1998) J. Biomater. Sci. Polym. Ed., 9, p. 1207; Mcfarland, C.D., Filippis, C.D., Jenkins, M., Tunstell, A., Rhodes, N.P., Williams, D.F., Steele, J.G., (1998) J. Biomater. Sci. Polym. Ed., 9, p. 1277; Kopperschlager, G., Bohme, H.J., Hofmann, E., (1982) Adv. Biochem. Eng., 25, p. 101; Travis, J., Bowen, J., Tewksbury, D., Johnson, D., Pannell, R., (1976) Biochem. J., 157, p. 301; Leatherbarrow, R.L., Dean, P.D.G., (1980) Biochem. J., 189, p. 27; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., (2003) J. Biomater. Sci. Polym. Ed., 14, p. 439; Dockal, M., Carter, D.C., Ruker, F., (1999) J. Biol. Chem., 274, p. 29303; Ostuni, E., Yan, L., Whitesides, G.M., (1999) Colloid Surf. B-Biointerfaces, 15, p. 3; Ulman, A., (1991) An Introduction to Ultrathin Organic Films: From Langmuir-Blodgett to Self-Assembled, , Academic Press Inc: San Diego, CA, USA; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., (1989) J. Am. Chem. Soc., 111, p. 321; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., (1987) J. Am. Chem. Soc., 109, p. 3559; Sigal, G.B., Mrksich, M., Whitesides, G.M., (1998) J. Am. Chem. Soc., 120, p. 3464; Seigal, R.R., Harder, P., Dahint, R., Grunze, M., (1997) Anal. Chem., 69, p. 3321; López, G.P., Biebuyck, H.A., Harter, R., Kumar, A., Whitesides, G.M., (1993) J. Am. Chem. Soc., 115, p. 10774; Prime, K., Whitesides, G.M., (1991) Science, 252, p. 1164; Chinn, J.A., Horbett, T.A., Ratner, B.D., (1991) Thromb. Haemost., 65, p. 608; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., (1999) IEEE Trans. Magn., 35, p. 4361; Pale-Grosdemange, C., Simon, E.S., Prime, K.L., Whitesides, G.M., (1991) J. Am. Chem. Soc., 113, p. 12; Castner, D.G., Hinds, K., Grainger, D.W., (1996) Langmuir, 12, p. 5083; Lin, J.C., Chuang, W.H., (2000) J. Biomed. Mater. Res., 51, p. 413; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, p. 45; (1993) Iodine-125, a Guide to Radioiodination Techniques - Amersham Life Science, p. 64. , Amersham International plc, Amersham Place, Little Chalfont, Bucks. HP7 9NA, England; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of Biocompatibility Tests, p. 183. , edited by D. F. Williams (Harcover, CRC Pr); Du, Y.J., Cornelius, R.M., Brash, J.L., (2000) Colloid Surf. B-Biointerfaces, 17, p. 59; Beamson, G., Briggs, D., (1992) High Resolution XPS of Organic Polymers - The Scienta ESCA300 Database, , John Wiley & Sons Ltd, Chichester, England; htpp://www.lasurface.com/Tarlov, M.J., Burgess Jr., D.R.F., Gillen, G., (1993) J. Am. Chem. Soc., 115, p. 5305; Tegoulia, V.A., Cooper, S.L., (2000) J. Biom. Mater. Res., 50, p. 291; Ishida, T., Tsuneda, S., Nishida, N., Hara, M., Sasabe, H., Knoll, W., (1997) Langmuir, 13, p. 4638; Silver, J.H., Hergenrother, R.W., Lin, J.C., Lim, F., Lin, H.B., Okada, T., Chaudhury, M.K., Cooper, S.L., (1995) J. Biom. Mater. Res., 29, p. 535; Smith, T., (1980) J. Colloid. Interf. Sci., 75, p. 51; Tidwell, C.D., Ertel, S.I., Ratner, B.D., (1997) Langmuir, 13, p. 3404; Silin, V., Weetall, H., Vanderah, D., (1997) J. Colloid. Interf. Sci., 185, p. 94; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., (2003) J. Biom. Mater. Res., 67 A, p. 158; Schlereth, D.D., (1997) Sens. Actuator B-Chem., 43, p. 78; Mrksich, M., Grunwell, J.R., Whitesides, G.M., (1995) J. Am. Chem. Soc., 117, p. 12009; Hodneland, C.D., Lee, Y.S., Min, D.H., Mrksich, M., (2002) PNAS, 99, p. 5048; Malmsten, M., Lassen, B., (1994) J. Colloid. Interf. Sci., 166, p. 490; Feng, L., Andrade, J.D., (1994) Biomaterials, 15, p. 323; Bertilsson, L., Butt, H.J., Nelles, G., Schlereth, D.D., (1997) Biosens. Bioelectron., 12, p. 839
Keywords: Adsorption; Albumin; aqueous solution; article; Cell immobilization; cibacron blue f3ga; Contact angle; controlled study; Drug products; Ethylene Glycol; fibrinogen; functional group; Glycols; gold; human; human serum albumin; iodine 125; isotope labeling; ligand; macrogol; molecule; priority journal; protein assembly; protein binding; protein immobilization; protein structure; Proteins; radioassay; Self assembly; surface property; synthesis; tetra(ethylene glycol) undecanethiol; thiol; thiol derivative; unclassified drug; Water; X ray photoelectron spectroscopy

Albumin and fibrinogen adsorption on Cibacron blue F3G-A immobilised onto PU-PHEMA (polyurethane-poly (hydroxyethylmethacrylate)) surfaces - Martins, M.C.L.; Wang, D.; Ji, J.; Feng, L.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2003)
In the present work, it is intended to study the effect of Cibacron blue F3G-A (CB) immobilised onto PU-PHEMA (polyurethane-poly(hydroxyethylmethacrylate)) surfaces on protein adsorption and bacterial adhesion. CB immobilisation was carried out by covalent binding between its triazine ring and the hydroxyl groups of the polymer. Characterisation of the films was carried out by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FT-IR), contact angle measurements, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). CB efficiency was evaluated using radiolabelled albumin and fibrinogen from pure solutions, mixtures of both and plasma. Bacterial adhesion tests before and after albumin pre-coating were also performed. The presence of CB increases albumin and fibrinogen adsorption to PU-PHEMA surfaces. The incorporation of CB onto the PU-PHEMA surface also increases bacterial adhesion. Although albumin pre-coating decreases bacterial adhesion onto PU (67% decrease) and PU-PHEMA-CB (80%), bacterial adhesion is always lower on PU and PU-PHEMA surfaces than on PU-PHEMA-CB. These results demonstrate that, in contrast to what has been described for CB bound to dextran, CB immobilisation on PU-PHEMA surfaces presents low selectivity to albumin and increased bacterial adhesion relatively to PU and PU-PHEMA surfaces.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856203766652057PubMed ID: 12807146Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: cibacron blue f3ga, 12236-82-7, 53127-08-5; dextran, 87915-38-6, 9014-78-2; fibrinogen, 9001-32-5; polymacon, 25053-81-0, 25249-16-5, 98932-78-6; polyurethan, 61789-63-7; Albumins; Biocompatible Materials; Cibacron Blue F 3GA, 12236-82-7; Fibrinogen, 9001-32-5; Membranes, Artificial; Polyhydroxyethyl Methacrylate, 25249-16-5; TriazinesReferences: Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, J.L., (1996) Biomaterials Science - an Introduction to Materials in Medicine, , (Eds), Academic Press, San Diego, CA;Greco, R.S., (1994) Implantation Biology, the Host Response and Biomedical Devices, , (Ed.), CRC Press, Ann Arbour, MI; Sapatnekar, S., Anderson, J.M., (1999) Handbook of Biomaterials Evaluation. Scientific, Technical and Clinical Testing of Implant Materials, p. 353. , A. F. von Recum (Ed.), Taylor & Francis, Philadelphia, PA; Kottke-Marchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., (1998) Biomaterials, 10, p. 147; Keogh, J.R., Eaton, J.W., (1994) J. Lab. Clin. Med., 121, p. 537; Sapatnekar, S., Kieswetter, K.M., Merritt, K., Anderson, J.M., Cahalan, L., Verhoeven, M., Hendriks, M., Cahalan, P., (1995) J. Biomed. Mater Res., 29, p. 247; Paulsson, M., Kober, M., Freij-Larsson Stollenwerk, C., Wesslén, B., Ljungh, Å., (1993) Biomaterials, 14, p. 845; Kopperschlager, G., Bohme, H.J., Hofmann, E., (1982) Adv. Biochem. Eng., 25, p. 101; Travis, J., Bowen, J., Tewksbury, D., Johnson, D., Pannell, R., (1976) Biochem. J., 157, p. 301; Arica, M.Y., Testereci, H.N., Denizli, A., (1998) J. Chromatogr A., 799, p. 83; Denizli, A., Salih, B., Senel, S., Arica, M.Y., (1998) J. Appl. Polym. Sci., 68, p. 657; Martins, M.C.L., Wang, D., Ji, J., Feng, L., Barbosa, M.A., (2003) Biomaterials, 24. , (in press); Leatherbarrow, R.L., Dean, P.D.G., (1980) Biochem. J., 189, p. 27; Horbett, T.A., (1986) Techniques of Biocompatibility Tests, 2, p. 183. , D. F. Williams (Ed.), CRC Press, Boca Raton, FL; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., (2001) J. Biomed. Mater. Res., 55, p. 45; (1993) Iodine-125, A Guide to Radioiodination Techniques, 64. , Amersham Life Science; Schrader, B., (1995) Infrared and Raman Spectroscopy, , (Ed.), VCH, Weinheim; Lamba, N.M.K., Woodhouse, K.A., Cooper, S.L., (1998) Polyurethanes in Biomedical Applications, , (Eds), CRC Press, Boca Raton, FL; http://www.lasurface.com/Beamson, G., Briggs, D., (1992) High Resolution XPS of Organic Polymers - The Scienta ESCA300 Database, , (Eds), Wiley, Chichester; Morra, M., Cassinelli, C., (1995) J. Biomed. Mater. Res., 29, p. 39; Compagnini, A., Fisichella, S., Foti, S., Maccarrone, G., Saletti, R., (1996) J. Chromatogr. A, 736, p. 115; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Kasori, Y., Shiroya, T., Shimura, K., Mochizuki, A., (2000) Biomaterials, 21, p. 1471; Feng, L., Andrade, J.D., (1994) Biomaterials, 15, p. 323; Peters T., Jr., (1996) All About Albumin. Biochemistry, Genetics and Medical Applications, , (Ed.), Academic Press, San Diego, CA; Dockal, M., Carter, D.C., Rüker, F., (1999) J. Biol. Chem., 274, p. 29303; Denizli, A., Kocakulak, M., Piskin, E., (1998) J. Chromatogr. B., 707, p. 25; Salih, B., Zenobi, R., (1998) Anal. Chem., 70, p. 1536; Österberg, E., Bergström, K., Holmberg, K., Schuman, T.P., Riggs, J.A., Burns, N.L., (1995) J. Biomed. Mater. Res., 29, p. 741; Beeskow, T., Kroner, K.H., Anspach, F.B., (1997) J. Colloid. Interf. Sci., 196, p. 278; Frazier, R.A., Matthijs, G., Davies, M.C., Roberts, C.J., Schacht, E., Tendler, S.J.B., (2000) Biomaterials, 21, p. 957; Bertilsson, L., Butt, H.J., Nelles, G., Schlereth, D.D., (1997) Biosens. Bioelectron., 12, p. 839; Kao, J.M., Rose, R., Yousef, M., Hunter, S.K., Rodgers, V.G.J., (1999) J. Biomed. Mater. Res., 47, p. 537; Tegoulia, V.A., Cooper, S.L., (2002) Colloid. Surf. B: Biointerf., 24, p. 217
Keywords: Adsorption; Albumin; Albumins; article; Bacterial adhesion; bacterium adherence; Biocompatible Materials; Chemical structure; Cibacron blue; cibacron blue f3ga; Contact angle; controlled study; covalent bond; dextran; fibrinogen; hydroxyl group; immobilization; infrared spectroscopy; isotope labeling; Membranes, Artificial; Microscopy, Electron, Scanning; nonhuman; PHEMA; Polyhydroxyethyl Methacrylate; polymacon; polyurethan; priority journal; Protein adsorption; Scanning electron microscopy; Spectroscopy, Fourier Transform Infrared; Staphylococcus epidermidis; Surface Properties; triazine derivative; Triazines; X ray photoelectron spectroscopy; XPS

Albumin and fibrinogen adsorption on PU-PHEMA surfaces - Martins, M.C.L.; Wang, D.; Ji, J.; Feng, L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2003)
Materials that adsorb specific proteins may find a variety of applications in the biomedical field. The aim of this study was the preparation of a hydrophilic surface, with low protein adsorption, to be used in the future as a support for the immobilisation of several species, e.g. Cibacron Blue F3G-A, which has been described to induce specific albumin adsorption. Poly(hydroxyethylmethacrylate) (PHEMA) and poly(hydroxyethylacrylate) (PHEA) were chosen as the hydrophilic surface because they can be easily polymerised and possess hydroxyl groups that can be used for the immobilisation of different compounds. Thin films of PHEMA and PHEA were successfully graft polymerised onto the surface of a commercial poly(etherurethane) (PU) using ceric ion as initiator. Grafting polymerisations were followed by mass gain and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). Since stability tests demonstrated that only PU-PHEMA was stable in alkaline solutions, a necessary condition to future immobilisations, the investigation was focused on the coating of PU with PHEMA. PU-PHEMA films were characterised in detail using several techniques as mass gain, ATR-FTIR, contact angle measurements, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). Protein adsorption was evaluated using radiolabelled albumin and fibrinogen from pure solutions and from mixtures of both proteins. PU surfaces modified with PHEMA have demonstrated low protein adsorption, showing their potential use as substrates. This opens the possibly of exploring the advantages of selective adsorption by appropriate immobilisation of specific molecules. © 2003 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00002-4PubMed ID: 12628827Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; Laboratório de Biomateriais, Inst. de Engenharia Biomédica, Rua do Campo Algre 823, Porto 4150-180, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: acrylic acid ethyl ester, 140-88-5; fibrinogen, 9001-32-5; poly(2 hydroxyethyl acrylate), 26022-14-0; polyetherurethan, 76600-67-4; polymacon, 25053-81-0, 25249-16-5, 98932-78-6; protein, 67254-75-5; Albumins; Biocompatible Materials; Fibrinogen, 9001-32-5; poly(2-hydroxyethyl acrylate), 26022-14-0; Polyhydroxyethyl Methacrylate, 25249-16-5; Water, 7732-18-5References: Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, J.L., (1996) Biomaterials science - An introduction to materials in medicine, , CA, USA, San Diego: Academic Press;Greco, R.S., (1994) Implantation biology, the host response and biomedical devices, , Ann Arbour, USA: CRC Press; Sapatnekar, S., Anderson, J.M., Hemocompatibility: Effects on humoral elements (1999) Handbook of biomaterials evaluation, Scientific technical and clinical testing of implant materials, pp. 353-365. , A.F. von Recum. Philadelphia, PA, USA: Taylor & Francis; Lopez, G.P., Ratner, B.D., Tidwell, C.D., Haycox, C.L., Rapoza, R.J., Horbett, T.A., Glow discharge plasma deposition of tetraethylene glycol dimethyl ether for fouling-resistant biomaterials surfaces (1992) J Biomed Mater Res, 26, pp. 415-439; Johnston, E.E., Bryers, J.D., Ratner, B.D., Interactions between Pseudomonas Aeruginosa and plasma-deposited PEO-like thin films during initial attachment and growth (1997) ACS Polym Prep, 38, pp. 1016-1017; Kottke-Marchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the in vitro blood compatibility of Dacron arterial prostheses (1998) Biomaterials, 10, pp. 147-155; Sapatnekar, S., Kieswetter, K.M., Merritt, K., Anderson, J.M., Cahalan, L., Verhoeven, M., Hendriks, M., Cahalan, P., Blood-biomaterial interactions in a flow system in the presence of bacterial, effect of protein adsorption (1995) J Biomed Mater Res, 29, pp. 247-256; Paulsson, M., Kober, M., Freij-Larsson, C., Stollenwerk Wesslén, B., Ljungh, Å., Adhesion of staphylococci to chemically modified and native polymers, and the influence of preadsorbed fibronectin, vitronectin and fibrinogen (1993) Biomaterials, 14, pp. 845-853; Keogh, J.R., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 121, pp. 537-545; Keogh, J.R., Velander, F.F., Eaton, J.W., Albumin-binding surfaces for implantable devices (1992) J Biomed Mater Res, 26, pp. 441-456; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Kamath, K.R., Park, K., Surface modification of polymeric biomaterials by albumin grafting using y-radiation (1994) J Appl Biomater, 5, pp. 163-173; McFarland, C.D., Filippis, C.D., Jenkins, M., Tunstell, A., Rhodes, N.P., Williams, D.F., Steele, J.G., Albumin binding surfaces: In vitro activity (1998) J Biomat Sci Polymer Ed, 9, pp. 1239-1277; Ji, J., Feng, L., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin (2001) Biomaterials, 22, pp. 3015-3023; Tsai, C.C., Huo, H.H., Kulkarni, P., Eberhart, R.C., Biocompatible coatings with high albumin affinity (1990) ASAIO Trans, 36, pp. 307-M310; Bekos, E.J., Ranieri, J.P., Aebisher, P., Gardella J.A., Jr., Bright, F.V., Structural changes of bovine serum albumin upon adsorption to modified fluoropolymer substrates used for neural cell attachment studies (1995) Langmuir, 11, pp. 984-989; Bailly, A., Laurent, A., Lu, H., Elalami, I., Jacob, P., Mundler, O., Merland, J., Soria, C., Fibrinogen binding and platelet retention: Relationship with the thrombogenicity of catheters (1996) J Biomed Mater Res, 30, pp. 101-108; Montheard, J.P., Chatzopoulos, M., Chappard, D., 2-Hydroxyethyl methacrylate (HEMA): Chemical properties and applications in biomedical fields (1992) J M S-Rev Macromol Chem Phys, C32, pp. 1-34; Feng, X.D., Sun, Y.H., Qiu, K.Y., Reactive site and Mechanism of graft copolymerisation onto poly(ether urethane) with Ceric ion as initiator (1985) Macromolecules, 18, pp. 2105-2109; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, 2, pp. 183-214. , Williams DF, editor. Harcover: CRC Press; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125. A Guide to Radioiodination Techniques, p. 64. , Amersham Life Science, Little Chalfont, England: Amersham International plc; Schrader, B., (1995) Infrared and Raman spectroscopy: methods and applications, , Weinheim: VCH Publishers, Inc., (Federal Republic of German); Lamba, N.M.K., Woodhouse, K.A., Cooper, S.L., (1998) Polyurethanes in biomedical applications, , Boca Raton, FL, USA: CRC Press; Bandekar, J., Sawyer, A., FT-IR spectroscopic studies of polyurethanes: IV studies of the effect of the presence of processing aids on the hemocompatibility of polyurethanes (1995) J Biomater Sci Polym Ed, 7, pp. 485-501; Tingey, K.G., Andrade, J.D., McGary C.W., Jr., Zdrahala, R.J., Surface analysis of commercial biomedical polyurethanes (1988) Polymer surface dynamics, , Andrade JD, editor. New York: Plenum Press; Beamson, G., Briggs, D., (1992) High resolution XPS of organic polymers - the scienta ESCA300 database, , Chichester, England: Wiley; Hsiue, G., Lee, S., Wang, C., Shiue, M.H., Chang, P.C., Plasma-induced graft copolymerisation of HEMA onto silicone rubber and TPX film improving rabbit corneal epithelial cell attachment and growth (1994) Biomaterials, 15, pp. 163-171; Lee, J.H., Ju, Y.M., Lee, W.K., Park, K.D., Kim, Y.H., Platelet adhesion onto segmented polyurethane surfaces modified by PEO - And sulfonated PEO-containing block copolymer additives (1998) J Biomed Mater Res, 40, pp. 314-323; Morra, M., Occhiello, E., Garbassi, F., On the wettability of poly(2-hydroxyethylmetacrylate) (1992) J Colloid Interface Sci, 149, pp. 84-91; Morra, M., Cassinelli, C., Surface field of forces and protein adsorption behavior of poly(hydroxyethylmethacrylate) films deposited from plasma (1995) J Biomed Mater Res, 29, pp. 39-45; Elam, J., Nygren, Adsorption of coagulation proteins from whole blood on to polymer materials: Relation to platelet activation (1992) Biomaterials, 13, pp. 3-8; Chin, J.A., Horbett, T.A., Ratner, B.D., Baboon fibrinogen adsorption and platelet adhesion to polymeric materials (1991) Thromb Haemostas, 65, pp. 608-617; Horbett, T.A., Adsorption of proteins from plasma to a series of hydrophilic-hydrophobic copolymers. II Compositional analysis with the prelabeled protein technique (1981) J Biom Mater Res, 15, pp. 673-695; Garrett, Q., Chatelier, R.C., Griesser, H.J., Milthorpe, B.K., Effect of charged groups on the adsorption and penetration of proteins onto and into carboxymethylated poly(HEMA) hydrogels (1998) Biomaterials, 19, pp. 2175-2186; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isoterms, competitivity, desorption and exchange of albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333; Bohnert, J.L., Horbett, T.A., Changes in adsorbed fibrinogen and albumin interactions with polymers indicated by decreases in detergent elutability (1986) J Colloid Interface Sci, 111, pp. 363-377; Slack, S.M., Horbett, T.A., Changes in fibrinogen adsorbed to segmented polyurethanes and hydroxyethylmethacrylate-ethylmethacrylate copolymers (1992) J Biom Mater Res, 26, pp. 1633-1649; Tanaka, M., Motomura, T., Kawada, M., Anzai, T., Kasori, Y., Shiroya, T., Shimura, K., Mochizuki, A., Blood compatible aspects of poly(hydroxyethylacrylate) (PMEA) - Relationship between protein adsorption and platelet adhesion on PHEA surface (2000) Biomaterials, 21, pp. 1471-1481; Vroman, L., Adams, A.L., Fisher, G.C., Munoz, P.C., Interaction of high molecular weight kininogen, Factor XII and fibrinogen in plasma at interfaces (1980) Blood, 55, pp. 156-159; Vroman, L., Adams, A.L., Adsorption of proteins out of plasma and solutions in narrow spaces (1986) J Colloid Interface Sci, 111, pp. 391-402; Andrade, J.D., Hlady, V., Protein adsorption and materials biocompatibility: A tutorial review and suggested hypotheses (1986) Adv Polym Sci, 79, pp. 1-63; Andrade, J.D., Hlady, V., Vroman effects, techniques and philosophies (1991) J Biomater Sci Polym Ed, 2, pp. 161-172; Brash, J.L., Studies of protein adsorption relevant to blood compatible materials (1991) Modern aspects of protein adsorption on biomaterials, p. 23. , Y.F. Missirlis, & W. Lemm. Kluwer Netherland: Academic Publishers; Brash, J.L., Hove, P.T., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polymer Ed, 4, pp. 591-599
Keywords: acrylic acid ethyl ester; Adsorption; Albumin; Albumins; article; ATR-FTIR; Biocompatible Materials; Chemical modification; Dose-Response Relationship, Drug; fibrinogen; film; Fourier transform infrared spectroscopy; Graft polymerisation; Humans; Hydrogen-Ion Concentration; Hydrophilic surfaces; hydrophilicity; hydroxyl group; infrared spectroscopy; isotope labeling; Microscopy, Electron, Scanning; molecular stability; Pellethane; PHEMA; poly(2 hydroxyethyl acrylate); polyetherurethan; Polyhydroxyethyl Methacrylate; polymacon; Polymerization; priority journal; protein; Protein adsorption; Proteins; Scanning electron microscopy; Spectrometry, X-Ray Emission; Spectroscopy, Fourier Transform Infrared; surface property; Thin films; unclassified drug; Water; X ray photoelectron spectroscopy

Cartographic representation of spatial data - De Pina, M.D.F. (Representação Cartográfica de Dados EspaciaisArquivos de MedicinaArq. Med., 2003)
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: ARQMELanguage of Original Document: PortugueseCorrespondence Address: De Pina, M.D.F.; INEB, Instituto de Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: fpina@ibmc.up.ptReferences: Tyner, J., (1992) Introduction to Thematic Cartography, , Prentice Hall;Dent, B., (1996) Cartography, Thematic Map Design, , WCB Publishers; Monmonier, M., (1993) Mapping It Out: Expository Cartography for the Humanities and Social Sciences, , The University of Chicago Press; Kraak, M.J., Ormeling, F.J., (1996) Cartography: Visualization of Spatial Data, , Longman; Burrough, P.A., McDonnell, R., (1998) Principles of Geographical Information Systems, , Oxford University Press
Keywords: article; cartography; diagram; dot map; epidemiological data; geographic distribution; histogram; population distribution; tuberculosis; visual aid

Constructing thromboresistant surface on biomedical stainless steel via layer-by-layer deposition anticoagulant - Tan, Q.; Ji, J.; Barbosa, M.A.; Fonseca, C.; Shen, J. (BiomaterialsBiomaterials, 2003)
Multilayer films consisting of polyethylenimine (PEI) and heparin were successfully prepared on biomedical 316L stainless steel surface via electrostatic self-assembly (ESA) of the PEI and heparin. The process of ESA of PEI/heparin was monitored by static contact angle, electrochemical impedance spectroscopy (EIS), reflection adsorption spectroscopy and X-ray photoelectron spectroscopy data. The contact angle and EIS data revealed that the multilayer coating was stable in Tris-HCl (pH 7.35) buffer solution for 21 days. The static platelet adhesion and static clotting time experiments indicated that the PEI/heparin-deposited stainless steel could resist the platelet adhesion and prolong the static clotting time effectively. Such an easy processing and shape-independent method may have good potential for surface modification of cardiovascular devices. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 67Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(03)00363-6PubMed ID: 12951013Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: heparin, 37187-54-5, 8057-48-5, 8065-01-8, 9005-48-5; polyethyleneimine, 74913-72-7; stainless steel, 12597-68-1; trometamol, 1185-53-1, 77-86-1; Anticoagulants; Coated Materials, Biocompatible; Heparin, 9005-49-6; Polyethyleneimine, 9002-98-6; Stainless Steel, 12597-68-1Manufacturers: AldrichReferences: Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., Ultrathin polymer coating by complexation of polyelectrolytes at interfaces: Suitable materials, structure and properties (2000) Macromol Rapid Commun, 21, pp. 319-348;Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu Rev Mater Sci, 26, pp. 153-187; Laschewsky, A., (1997) Eur Chem Chron ECC, 2, pp. 13-24; Picart, C., Lavalle, Ph., Hubert, P., Cuisnier, Fj., Decher, G., Schaaf, P., Voegel, J.C., Buildup mechanism for poly (L-lysine)/hyaluronic acid films onto a solid surface (2001) Langmuir, 17, pp. 7414-7424; Houska, M., Brynda, E., Interactions of proteins with polyelectrolytes at solid/liquid interfaces: Sequential adsorption of albumin and heparin (1997) J Colloid Interface Sci, 188, pp. 243-250; Brynda, E., Houska, M., Multiple alternating molecular layers of albumin and heparin on solid surfaces (1996) J Colloid Interface Sci, 183, pp. 18-25; Thomann, U.I., Uggowitzer, P.J., Wear-corrosion behavior of biocompatible austenitic stainless steels (2000) Wear, 239, pp. 48-58; Cheatham, J., Improved stents for pediatric applications (2001) Prog Pediatr Cardiol, 14, pp. 95-115; Donachie, M., Biomedical alloys (1998) Adv Mater Process, 154, pp. 63-65; Decher, G., Fuzzy nanoassemblies: Toward layered polymeric multicomposites (1997) Science, 277, pp. 1232-1237; Raposo, M., Pontes, R.S., Mattoso, L.H.C., Oliveira, O.N., Kinetics of adsorption of poly (o-methoxyaniline) self-assembled films (1997) Macromolecules, 30, pp. 6095-6101; Vov, Y.L., Rusling, J., Thomsen, D.L., Papadimitrakopoulos, F., Kawakami, T., Kunitake, T., High-speed multilayer film assembly by alternate adsorption of silica nanoparticles and linear polycation (1998) Chem Commun, 11, pp. 1229-1230; Lowack, K., Helm, C.A., Controlling the self-assembly process of polyelectrolyte multilayers (1998) Macromolecules, 31, pp. 823-833; Cheng, Z., Cheng, L., Dong, S., Yang, X., Formation and characterization of heteropolyacid/polycation multilayer films on gold electrode (2001) J Electrochem Soc, 148, p. 227
Keywords: 316L stainless steel; Adhesion; Adsorption; anticoagulant agent; Anticoagulants; aqueous solution; article; Biocompatibility; biomaterial; Biomaterials; blood clotting time; Blood Platelets; Blood-compatibility; buffer; Coated Materials, Biocompatible; coating; Coatings; Contact angle; controlled study; Deposition; device; electricity; Electrochemical impedance spectroscopy; electrochemistry; Electrostatics; heparin; human; human cell; Humans; implant; Layer-by-layer; material coating; materials testing; Multilayers; Organic polymers; pH; Platelet Adhesiveness; Polyethyleneimine; priority journal; reflection adsorption spectroscopy; Self assembly; Spectroscopy; Stainless steel; Surface Properties; surface property; Surfaces; thrombocyte adhesion; Thromboresistant surfaces; trometamol; X ray photoelectron spectroscopy

Corrosion behaviour of commercially pure titanium shot blasted with different materials and sizes of shot particles for dental implant applications - Aparicio, C.; Javier Gil, F.; Fonseca, C.; Barbosa, M.; Planell, J.A. (BiomaterialsBiomaterials, 2003)
It is well known that the osseointegration of the commercially pure titanium (c.p. Ti) dental implant is improved when the metal is shot blasted in order to increase its surface roughness. This roughness is colonised by bone, which improves implant fixation. However, shot blasting also changes the chemical composition of the implant surface because some shot particles remain adhered on the metal. The c.p. Ti surfaces shot blasted with different materials and sizes of shot particles were tested in order to determine their topographical features (surface roughness, real surface area and the percentage of surface covered by the adhered shot particles) and electrochemical behaviour (open circuit potential, electrochemical impedance spectroscopy and cyclic polarisation). The results demonstrate that the increased surface area of the material because of the increasing surface roughness is not the only cause for differences found in the electrochemical behaviour and corrosion resistance of the blasted c.p. Ti. Among other possible causes, those differences may be attributed to the compressive residual surface stresses induced by shot blasting. All the materials tested have an adequate corrosion and electrochemical behaviour in terms of its possible use as dental implant material. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 77Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00314-9Language of Original Document: EnglishCorrespondence Address: Aparicio, C.; Res. Center in Biomed. Eng. (CREB), Department of Materials Science, Universitat Politecnica de Catalunya, Av. Diagonal 647, 08028 Barcelona, Spain; email: conrado.aparicio@upc.esChemicals/CAS: Dental Implants; Titanium, 7440-32-6References: Brånemark, P.I., Hansson, B.O., Adell, R., Breine, U., Lindström, J., Hallen, O., Öhman, A., Osseointegrated implants in the treatment of edentulous jaw experience from a 10-year period (1977) Scand J Reconstr Surg, 16 (SUPPL.), pp. 1-132;Lemons, J.E., Application of materials in medicine and dentistry. Dental implants (1996) Biomaterials Science: An Introduction to Materials in Medicine, pp. 308-318. , B.D. Ratner, A.S. Hoffman, F.J. Schoen, & J.E. Lemons. San Diego: Academic Press; Pourbaix, M., Electrochemical corrosion of metallic biomaterials (1984) Biomaterials, 5, pp. 122-134; Bardos, D.I., Titanium and titanium alloys (1990) Encyclopaedia of Medical and Dental Materials, pp. 360-365. , D. William. Oxford: Pergamon Press; Boyer, R., Welsh, G., Colling, E.W., (1994) Materials Properties Handbook: Titanium Alloys, pp. 181-219. , Ohio: ASM International; Kasemo, B., Lausmaa, J., Surface science aspects on inorganic biomaterials (1986) CRC Crit Rev Biocompatibilty, 4, pp. 335-380; Tengvall, P., Lundtröm, I., Physico-chemical considerations of titanium as a biomaterial (1992) Biomaterials, 9, pp. 115-134; Albrektsson, T., Brånemark, P.I., Hansson, B.O., Lindström, J., Osseointegrated titanium implants (1981) Acta Orthop Scand, 52, pp. 155-170; Thomas, K.A., Cook, S., An evaluation of variables influencing implant fixation by direct bone apposition (1985) J Biomed Mater Res, 19, pp. 875-901; Wennerberg, A., (1996) On Surface Roughness and Implant Incorporation, , Ph.D. thesis, Göteborg: University of Göteborg; Bowers, K.T., Keller, J.C., Randolph, B.A., Wick, D.G., Michaels, C.M., Optimization of surface micromorphology from enhanced osteoblast response in vitro (1992) Int J Oral Maxillofac Implants, 7, pp. 302-310; Groessner-Schereider, B., Tuan, R.S., Enhanced extracellular matrix production and mineralization by osteoblasts cultured on titanium surfaces in vitro (1992) J Cell Sci, 101, pp. 209-217; Schwartz, Z., Boyan, B.D., Underlaying mechanisms at the bone biomaterial interface (1994) J Cell Biochem, 56, pp. 340-347; Boyan, B.D., Hummert, T.W., Kieswetter, K., Schraub, D., Dean, D.D., Schwartz, Z., Effect of titanium surface characteristics on chondrocytes and osteoblasts in vitro (1995) Scanning Electron Microsc (Cells and Materials), 5, pp. 323-335; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., Effect of titanium surface roughness on proliferation, differentiation and protein synthesis of human osteoblast-like cells (MG63) (1995) J Biomed Mater Res, 29, pp. 389-401; Ong, J.L., Prince, C.W., Raikar, G.N., Lucas, L.C., Effect of surface topography of titanium on surface chemistry and cellular response (1996) Implant Dent, 5, pp. 83-88; Deligianni, D.D., Katsal, N., Ladas, S., Sotiropoulou, D., Amedee, J., Missirlis, Y.F., Effect of surface roughness of the titanium alloy Ti-6Al-4V on human bone marrow cell response and on protein adsorption (2001) Biomaterials, 22, pp. 1241-1251; Schwartz, Z., Lohmann, C.H., Sisk, M., Cochran, D.L., Sylvia, V.L., Simpson, J., Dean, D.D., Boyan, B.D., Local factor production by MG63 ostoblast-like cells in response to surface roughness and 1,25-(OH) 2D 3 is mediated via protein kinase C- and protein kinase A-dependent pathways (2001) Biomaterials, 22, pp. 731-741; Predecki, P., Stephan, J.E., Auslander, B.A., Mooney, V.L., Kirkland, K., Kinetics of bone growth into cylindrical channels in aluminium oxide and titanium (1972) J Biomed Mater Res, 6, pp. 375-400; Buser, D., Schenk, R.K., Steinemann, S., Fiorelini, J.P., Fox, C.H., Stich, H., Influence of surface characteristics on bone integration of titanium implants. A histomorphometric study in miniature pigs (1991) J Biomed Mater Res, 25, pp. 889-902; Ericsson, I., Johansson, C., Bystedt, H., Norton, M.R., A histomorphometric evaluation of bone-to-implant contact on machined-prepared roughened titanium dental implants (1994) Clin Oral Implant Res, 5, pp. 202-206; Feighan, J.E., Goldberg, V.M., Davy, D., Parr, J.A., Stevenson, S., The influence of surface-blasting on the incorporation of titanium alloy implants in a rabit intramedullary model (1995) J Bone Jt Surg Am, 77, pp. 1380-1395; Wennerberg, A., Albrektsson, T., Andersson, B., An animal study of c.p. titanium screws with different surface topographies (1995) J Mater Sci: Mater Med, 6, pp. 302-309; Wong, M., Eulenberger, J., Schenk, R., Hunziker, E., Effect of surface topology on the osseointegration of implant materials in trabecular bone (1995) J Biomed Mater Res, 29, pp. 1567-1575; Wennerberg, A., Albrektsson, T., Johansson, C., Andersson, B., Experimental study of turned and grit-blasted screw-shaped implants with special emphasis on effects of blasting material and surface topography (1996) Biomaterials, 17, pp. 15-22; Cochran, D.L., Schenk, R.K., Lussi, A., Higginbottom, F.L., Buser, D., Bone response to unloaded and loaded titanium implants with a sandblasted and acid etched surface: A histometric study in the canine mandible (1998) J Biomed Mater Res, 40, pp. 1-11; Piatelli, A., Manzon, L., Scarano, A., Paolantonio, M., Piatelli, M., Histologic and histomorphometric analysis of the bone response to machined and sandblasted titanium implants: An experimental study in rabbits (1998) Int J Oral Maxillofac Implants, 13, pp. 805-810; Svehla, M., Morberg, P., Zicat, B., Bruce, W., Sonnabend, D., Walsh, W.R., Morphometric and mechanical evaluation of titanium implant integration: Comparison of five surface structures (2000) J Biomed Mater Res, 51, pp. 15-22; Gotfredsen, K., Nimb, L., Hjorting-Hansen, E., Jensen, J.S., Holmen, A., Histomorphometric and removal torque analysis for TiO 2-blasted titanium implants (1994) Clin Oral Implant Res, 5, pp. 202-206; Jones, F., Teeth and bones: Applications of surface science to dental materials and related biomaterials (2001) Surf Sci Rep, 42, pp. 75-205; Naji, A., Harnad, M.F., Cytocompatibility of two coating materials, amorphous alumina and silicon carbide, using human differentiated cell cultures (1991) Biomaterials, 12, pp. 690-694; Darvell, B.W., Samman, N., Luk, W.K., Clark, K.F., Tideman, H., Contamination of titanium casting by aluminium oxide blasting (1995) J Dent, 23, pp. 319-322; Placko, H.E., Mishra, S., Weimer, J.J., Lucas, L.C., Surface Characterization of titanium-based implant materials (2000) Int J Oral Maxillofac Implants, 15, pp. 355-363; Orsini, G., Assenza, B., Scarano, A., Piatelli, M., Piatelli, A., Surface analysis of machined versus sandblasted and acid-etched titanium implants (2000) Int J Oral Maxillofac Implants, 15, pp. 779-784; Gross, U., Strunz, V., The interface of various glasses and glass ceramics with a bony implantation bed (1985) J Biomed Mater Res, 19, pp. 251-271; Aparicio, C., Gil, F.J., Peraire, C., Padrós, A., Planell, J.A., Effect of size and material of the shot peening particles on adhesion and differentiation of osteoblast-like cell cultures on commercially pure titanium (1998) North Sea Biomaterials 1998 Proceedings, p. 137. , The Hague; Fontana, M.G., Green, N.D., (1978) Corrosion Engineering: Mc Graw Hill Series in Materials Science and Engineering, , USA: McGraw-Hill; Standard practice for laboratory immersion corrosion testing metals (1992) 1992 Annual Book of ASTM Standards, pp. 102-109. , vol. 03.02. Philadelphia: ASTM; Boukamp, B.A., (1989) Equivalent Circuit (EQUIVCRTPAS). User's Manual, , Enschede: University of Twente; Standard test method for conducting cyclic potentiodynamic polarization measurements for localized corrosion susceptibility of iron-nickel, or cobalt-based alloys (1992) 1992 Annual Book of ASTM Standards, pp. 231-235. , vol. 03.02. Philadelphia: ASTM; (1984) Norme FEPA des Grains de Corindon Electrofondu et de Carbure de Silicium Pour Abrasifs Agglomeres, , Paris: Fedération Européenne des Fabricants de Produits Abrasifs; Bohn, P., Qualitaty control of shot media by sieve analysis (1999) Shot Peener, 13, pp. 6-9; Mehelich, C.S., Van Kuiken, L., Woelfel, M.M., Shot peening (1995) ASM Metals Handbook. Vol. 5: Surface Engineering, 5, pp. 138-149. , USA: ASM International; Udupa, G., Singaperumal, M., Sirohi, R.S., Kothiyal, M.P., Characterization of surface topography by confocal microscopy: II. The micro and macro surface irregularities (2000) Meas Sci Technol, 11, pp. 315-329; Arnell, R.D., Davie, P.B., Halling, J., Whomes, T.L., (1991) Tribology: Principles and Design Applications, , London: Mac Millan; Udupa, G., Singaperumal, M., Sirohi, R.S., Kothiyal, M.P., Characterization of surface topography by confocal microscopy: I. Principles and the measurement system (2000) Meas Sci Technol, 11, pp. 305-314; Solar, R.J., Pollack, S.R., Korostoff, E., In vitro corrosion testing of titanium surgical implant alloys: An approach to understanding titanium release from implants (1979) J Biomed Mater Res, 13, pp. 217-250; Hoar, T.P., Mears, D.C., Corrosion resistant alloys in chloride solutions, materials for surgical implants (1966) Proc Royal Soc London Ser A, 294, pp. 486-510; Gonzalez, J.E.G., Mirza-Rosca, J.C., Study of the corrosion behaviour of titanium and some of its alloys for biomedical and dental implant applications (1999) J Electroanal Chem, 471, pp. 109-115; McDonald, J.R., (1987) Impedance Spectroscopy, , New York: Wiley; Aziz-Kerrzo, M., Conroy, K.G., Fenelson, A.M., Farrell, S.T., Breslin, C.B., Electrochemical studies on the stability and corrosion resistance of titanium-based implant materials (2001) Biomaterials, 22, pp. 1531-1539; Cai, Z., Nakajima, H., Woldu, M., Berglund, A., Bergman, M., Okabe, T., In vitro corrosion resistance of titanium made using different fabrication methods (1999) Biomaterials, 20, pp. 183-190; Kobayashi, M., Matsui, T., Murakami, Y., Mechanism of creation of compressive residual stresses by shot peening (1998) Int J Fatigue, 20, pp. 351-357; Prevey, P.S., X-ray diffraction characterization of residual stresses produced by shot peening (2001) Shot Peener, 15, pp. 4-8; Mueller, H.J., Greener, E.H., Polarization studies of surgical materials in Ringer's solution (1970) J Biomed Mater Res, 4, pp. 29-41; Speck, K.M., Fraker, A.C., Anodic polarization behavior of Ti-Ni and Ti-6Al-4V in simulated physiological solution (1980) J Dent Res, 59, pp. 1590-1595; Sousa, S.R., Barbosa, M.A., Corrosion resistance of titanium cp in saline physiological solutions with calcium phosphate and proteins (1993) Biomaterials, 14, pp. 287-294; Khan, M.A., Williams, R.L., Williams, D.F., In-vitro corrosion and wear of titanium alloys in the biological environment (1996) Biomaterials, 17, pp. 2117-2126; Ewers, G.J., Greener, E.H., The electrochemical activity of the oral cavity - A new approach (1985) J Oral Rehab, 12, pp. 469-476
Keywords: article; Blast finishing; chemical composition; chemistry; Corrosion; Dental implant; Dental Implants; Dental prostheses; Electric Potential; Electrochemical impedance spectroscopy; electrochemistry; impedance; materials testing; Particle Size; Polarization; priority journal; Shot blasting; Spectroscopy; stress; Surface roughness; Surface topography; Titanium; tooth implantation

Creating maps: The construction of a lecture on the specialties of phenomena - Henrique Castiglione, L.; De Fátima De Pina, M. (Elaborar Mapas: A Construção de um Discurso sobre a Espacialidade dos FenómenosArquivos de MedicinaArq. Med., 2003)
Keywords: audiovisual equipment; geography; information processing; interpersonal communication; medical education; medical specialist; review

Detection and validation of lung field contours on chest radiographs - Mendonça, A.M.; Alves Da Silva, J.; Campilho, A. (Proceedings of the IASTED International Conference on Biomedical EngineeringProc. IASTED Internat. Conf. Biomed. Eng., 2003)
The purpose of the research herein presented is the automatic detection of lung boundaries in posterior-anterior digital chest radiographs. The precise location of the two lungs is important in a computer-aided diagnosis system as it allows the reduction of the region under analysis, decreasing the computation time and facilitating data compression. Furthermore, it allows the delimitation of the search area, easing the selective tuning of the abnormalities detection algorithms. The results produced by the automatic method were validated by comparison with manual contours traced by an experienced radiologist. For this particular purpose, two programs with friendly interfaces were developed. The achieved comparison results demonstrate the good performance of the automatic method.
Conference code: 63063Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Mendonça, A.M.; INEB, Inst. de Engenharia Biomédica, Campus da FEUP, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: amendon@fe.up.ptReferences: Tsujii, O., Freedman, M., Mun, S., Automated segmentation of anatomic regions in chest radiographs using an adaptive-sized hybrid neural network (1998) Medical Physics, 25, pp. 998-1007;Armato III, S., Giger, M., MacMahon, H., Computerized detection of abnormal asymetry in digital lateral chest radiographs (1994) Medical Physics, 21, pp. 1761-1768; Armato III, S., Giger, M., Ashizawa, K., MacMahon, H., Automated lung segmentation in digital lateral chest radiographs (1998) Medical Physics, 25, pp. 1507-1520; Carrascal, F., Carreira, J., Souto, M., Automatic calculation of total lung capacity from automatically traced lung boundaries in posterior-anterior and lateral digital chest radiographs (1998) Medical Physics, 25, pp. 1118-1131; Ginneken, B., Romeny, B., Automatic segmentation of lung fields in chest radiographs (2000) Medical Physics, 27, pp. 2445-2455; Li, L., Zheng, Y., Kallergi, M., Clark, R., Improved method for automatic identification of lung regions on chest radiographs (2001) Academic Radiology, 8, pp. 629-638; Monteiro, M., Mendonça, A.M., Campilho, A., Lung field detection on chest radiographs (2002) Proceedings of VIIP02, IASTED International Conference on Visualization, Imaging and Image Processing, pp. 367-372. , J. Villanueva (ed): Spain Sponsors: IASTED
Keywords: Algorithms; automation; Biological organs; Chest radiographs; Computational time; Computer aided diagnosis; Computer-aided diagnosis; Data compression; Image analysis; Medical image processing; Medical imaging; Radiography; Regions of interest (ROI)

Development of foetal and neonatal simulators at the University of Porto - van Meurs, W.L.; Sá Couto, P.M.; Sá Couto, C.D.; Bernardes, J.F.; Ayres-de-Campos, D. (Medical Education, SupplementMed. Educ. Suppl., 2003)
Background: Human error can be expected to play a significant role in adverse outcomes in perinatal acute care. In acute care of the adult, simulator based training is recommended and used to improve patient safety. Aims: Our general goal is to develop model-driven foetal and neonatal educational simulators and curricula. The specific objectives of this paper are to introduce the reader to the perinatal acute care context and simulator design considerations, as well as to give initial results and describe ongoing developments. A brief description of adult simulators and simulation engines is followed by a more detailed description of a foetal distress simulator (FDS) and of models for a neonatal simulator developed at the University of Porto. Ongoing developments involve the modelling of foetal baroreflexes, the effect of uterine contractions, and an adapted method for estimating foetal heart rate variability parameters. Results: We present FDS simulation results reflecting the changes in oxygen supply to the foetus and the foetal heart rate in response to a reduction in uterine blood flow. We also present a structural diagram of a model for the educational simulation of congenital heart disease and preliminary simulation results reflecting a patent ductus arteriosus. Conclusion: We expect that, after initial clinical and educational validation, the presented models and simulators will play a role in simulator-based educational programmes contributing to increased perinatal safety.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: MESECPubMed ID: 14641636Language of Original Document: EnglishCorrespondence Address: Van Meurs, W.L.; INEB - Inst. de Engenharia Biomedica, Lab. de Sinal e Imagem Biomedica, Edificio I-Poente, Rua Roberto Prias, s/n, 4200-465 Porto, Portugal; email: wvanmeurs@ineb.up.ptChemicals/CAS: oxygen, 7782-44-7References: Kohn, L.T., Corrigan, J.M., Donaldson, M.S., (2000) To Err Is Human, Building a Safer Health Care System, , Washington, DC: National Academic Press;Denson, J.S., Abrahamson, S., A computer-controlled patient simulator (1969) JAMA, 208, pp. 504-508; Gaba, D.M., DeAnda, A., A comprehensive anesthesia simulation environment. Re-creating the operating room for research and training (1988) Anesthesiology, 69, pp. 387-394; Good, M.L., Gravenstein, J.S., Anesthesia simulators and training devices (1989) Int Anesthesiol Clin, 27, pp. 161-168; Gaba, D., Howard, S., Fish, K., Smith, B., Sowb, Y., Simulation-based training in anesthesia crisis resource management (ACRM): A decade of experience (2001) Simulation Gaming, 32, pp. 175-193; Gordon, J.A., 'Practicing' medicine without risk: Students' and educators' responses to high-fidelity patient simulation (2001) Acad Med, 76, pp. 469-472; Ma, O., Simulation saves lives (2001) Newsletter of the American Society of Anesthesiologists, , Park Ridge: American Society of Anesthesiologists; October; Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324; Van Meurs, W.L., Nikkelen, E., Good, M.L., Pharmacokinetic-pharmacodynamic model for educational simulations (1998) IEEE Trans Biomed Eng, 45, pp. 582-590; Öhrn, M.A.K., Van Oostrom, J.H., Van Meurs, W.L., A comparison of traditional textbook and interactive computer learning of neuromuscular block (1997) Anesth Analg, 84, pp. 657-661; Euliano, T.Y., Caton, D., Van Meurs, W.L., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) J Clin Monit, 13, pp. 293-297; Sá Couto, P.M., Van Meurs, W.L., Bernardes, J.F., Marques De Sá, J.P., Goodwin, J.A., Mathematical model for educational simulation of the oxygen delivery to the fetus (2002) Cont Eng Prac, 10, pp. 59-66; Sá Couto, P.M., Van Meurs, W.L., Bernardes, J.F., Marques De Sá, J.P., Goodwin, J.A., Combined model-driven and rule-based approach for educational simulation of fetal heart rate (2002) BIOSIGNAL 2002. Proceedings of the 16th Biennial International Conference of the European Association for Speech, Signal and Image Processing (EURASIP), 26-28 June 2002, Brno, Czech Republic, pp. 400-402. , Jan J, Kozumplík J, Provazník I, eds. Brno: Vutium Press; Itskovitz, J., LaGamma, E.F., Rudolph, A.M., Heart rate and blood pressure responses to umbilical cord compression in fetal lambs with special references to the mechanism of variable deceleration (1983) Am J Obstet Gynecol, 147, pp. 451-457; Lee, S.T., Hon, E.H., Fetal hemodynamic response to umbilical cord compression (1963) J Obstet Gynecol, 22, pp. 553-562; Goodlin, R.C., Lowe, E.W., A functional umbilical cord occlusion heart rate pattern - The significance of overshoot (1974) Obstet Gynecol, 43, pp. 22-30; Scheffs, J., Vasicka, A., Li, C., Solomon, N., Siler, W., Uterine blood flow during labor (1971) Obstet Gynecol, 38, pp. 15-24; Brotanek, V., Hendricks, C.H., Yoshida, T., Importance of changes in uterine blood flow in initiation of labor (1969) Am J Obstet Gynecol, 105, pp. 535-546; Butler, L.A., Longo, L.D., Power, G.G., Placental blood flows and oxygen transfer during uterine contractions: A mathematical model (1976) J Theor Biol, 61, pp. 81-95; Felgueiras, C., Marques De Sá, J.P., Bernardes, J., Gama, S., Classification of foetal heart rate sequences based on fractal features (1998) Med Biol Eng Comput, 36, pp. 197-201; Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Graphical and mathematical representation of congenital heart disease (2002) Proceedings of the SESAM Annual Meeting, 10-11 May 2002; Centro de Entrenamiento en Situaciones Críticas, Santander, Spain, p. 18; Beneken, J.E.W., (1965) A Mathematical Approach to Cardiovascular Function: The Uncontrolled Human System, , PhD dissertation. Utrecht, The Netherlands: Rijksuniversiteit Utrecht; Huikeshoven, F., Coleman, T.G., Jongsma, H.W., Mathematical model of the fetal cardiovascular system: The uncontrolled case (1980) Am J Physiol, 239, pp. R317-25; Klaus, M.H., Fanaroff, A.A., (2001) Care of the High-Risk Neonate, 5th Edn., , Philadelphia: WB Saunders
Keywords: article; audiovisual equipment; blackstarPatient simulation; clinical competence; Clinical competence/blackstarstandards/economics; competence; Curriculum; Education, Medical, Undergraduate; Education, medical, undergraduate/blackstarmethods; Equipment Safety; fetus distress; human; Humans; Manikins; medical education; model; oxygen; Patient Simulation; perinatal care; Perinatal care/ blackstarstandards/methods; Portugal; safety; simulator; training

Dissolution studies of hydroxyapatite and glass-reinforced hydroxyapatite ceramics - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J.; Prado da Silva, M.H. (Materials CharacterizationMater Charact, 2003)
In the continuous agitation assays, glass-reinforced hydroxyapatite (GR-HA) was shown to form a calcium phosphate (CaP) layer, but hydroxyapatite (HA) only formed dispersed precipitates. The formation of this layer was first detected on the GR-HA with a 7.5% glass addition (7.5 GR-HA) after only 3 days of immersion in simulated body fluid (SBF). The time required for layer formation decreased as the amount of glass added to the HA increased. The dissolution rate of the materials followed a similar pattern, i.e. the dissolution rate for GR-HA was higher than for HA, and increased with the addition of glass. The immersion of 7.5 GR-HA in water showed almost linear dissolution kinetics over the immersion periods (3, 7, 15, 30 and 60 days). The concentration of calcium ions in solution and the scanning electron microscopy (SEM) analysis of the 7.5 GR-HA specimens immersed in water and in SBF revealed a clear competition between the material dissolution and the precipitation of a CaP phase. Fourier transformed infrared spectroscopy with alternated total reflectance (FTIR-ATR) analysis indicated that the CaP phase that formed during longer immersion times (30 and 60 days) could be a carbonate-substituted CaP precipitate. As expected from previous work, the GR-HA behavior in terms of its in vitro bioactivity is higher than HA because a homogeneous CaP layer is formed and the precipitation occurs faster. From the dissolution test and in accordance with the chemical composition of the samples, GR-HA was more soluble than HA. © 2003 Elsevier Inc. All rights reserved.
Conference code: 61615Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: MACHEdoi: 10.1016/S1044-5803(03)00092-5Language of Original Document: EnglishCorrespondence Address: Prado da Silva, M.H.; DEMP, UFC, Campus PICI, Bl. 714, Fortaleza, CE 60455-760, Brazil; email: mhprado@dem.ufc.brReferences: Barinov, S.M., Baschenko, Y.V., Application of ceramic composites as implants: Result and problem (1992) Bioceramics and the Human Body, pp. 206-210. , A. Ravaglioli, & A. Krajewski. United Kingdom: Elsevier;Nishihara, K., Studies on peri-root tissue formation around new type artificial root made of dense hydroxyapatite (1993) Clin. Mater., 12, pp. 159-167; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tensions, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J. Biomed. Mater. Res., 45, pp. 370-375; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O, MgO (1996) J. Mater. Sci. Mater. Med., 7, pp. 187-189; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of effects of glass on response of osteosarcoma cells to plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings (1999) J. Biomed. Mater. Res., 47, pp. 603-611; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation (1999) J. Biomed. Mater. Res., 45, pp. 376-383; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J. Biomed. Mater. Res., 54, pp. 463-469; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J. Biomed. Mater. Res., 41, pp. 649-656; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strength bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 331-343; Kokubo, T., Kushitani, H., Kitsugi, T., Yamamuro, T., Solution able to reproduce in vivo surface-structure changes of bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 721-734; Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., Features of calcium phosphate plasma-sprayed coatings: An in vitro study (1994) J. Biomed. Mater. Res., 28, pp. 961-967; Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., Calcium phosphate plasma-sprayed coatings and their stability: An in vivo study (1994) J. Biomed. Mater. Res., 28, pp. 909-917; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Yamamuro, T., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J. Mater. Sci. Mater. Med., 3, pp. 79-83; Zhang, H., Li, S., Yan, Y., Dissolution behaviour of hydroxyapatite powder in hydrothermal solution (2001) Ceram. Int., 27, pp. 451-454; LeGeros, R.Z., LeGeros, J.P., Calcium phosphate biomaterials in medical applications (1996) Bioceramics, 9, pp. 7-10. , T. Kokubo, T. Nakamura, & F. Miyaji. Otsu, Japan: Elsevier; Queiroz, A.C., Santos, J.D., Monteiro, F.J., Gibson, I.R., Knowles, J.C., Adsorption and release studies of sodium ampicillin from hydroxyapatite and glass-reinforced hydroxyapatite composites (2001) Biomaterials, 22, pp. 1393-1400; Langenbucher, F., Benz, D., Kürth, W., Möller, H., Otz, M., Standardized flow-cell method as an alternative to existing pharmacopoeial dissolution testing (1989) Pharm. Ind., 51 (11), pp. 1276-1281; Kokubo, T., (1990) CRC Handbook of Bioactive Ceramics, 1, p. 41. , T. Yamamuro, L.L. Hench, & J. Wilson. Boca Raton (FL): CRC Press; International Standard ISO/FDIS 10993-14, Biological evaluation of medical devices: Part 14 (2001) Identification and Quantification of Degradation Products from Ceramics
Keywords: Ceramic materials; Dissolution; glass; Glass-reinforced hydroxyapatite; hydroxyapatite; Immersion times; Scanning electron microscopy

Effect of heat treatment on relative content of β-Ca 2P 2O 7 crystalline phase in calcium phosphate glass-ceramics - Li, Y.; Weng, W.; Du, P.; Shen, G.; Han, G.; Santos, J.D.; Lopes, A.M. (Kuei Suan Jen Hsueh Pao/ Journal of the Chinese Ceramic SocietyKuei Suan Jen Hsueh Pao, 2003)
The 3Na 2O-12TiO 2-57CaO-28P 2O 5 glass was heat-treated to form glass-ceramics under different conditions. The relationships between the heat-treatment conditions and the content of β-Ca 2P 2O 7 in the glass-ceramics, bioactivity of the glass-ceramics were investigated. The experimental results show that the glass-ceramics contain crystalline phases of β-Ca 2P 2O 7, CaTi 4(PO 4) 6, NaTi 2(PO 4) 3 and TiP 2O 7 after heat-treatment, in which β-Ca 2P 2O 7 crystalline phase is a dominant one; the content of β-Ca 2P 2O 7 crystalline phase in the glass-ceramics increases with the increase of nucleation temperature and time; and the glass-ceramics with more β-Ca 2P 2O 7 crystalline phase has a better bioactivity. The role of heat-treatment in increasing the content of β-Ca 2P 2O 7 crystalline phase in the glass-ceramics is attributed to the crystallization of β-Ca 2P 2O 7 involved in the simultaneous occurrence of the glass phase separation and nucleation processes. Due to the better ability of β-Ca 2P 2O 7 in promoting bioactivity, the glass-ceramics with more β-Ca 2P 2O 7 phase have stronger bioactivity. Therefore, the bioactivity of the glass-ceramics could be changed by heat treatment.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KSYHALanguage of Original Document: ChineseCorrespondence Address: Li, Y.; Dept. of Mat. Sci. and Eng., Zhejiang Univ., Hangzhou 310027, ChinaReferences: Hench, L.L., Bioceramics (1998) J. Am. Ceram. Soc., 81, pp. 1705-1731;Kitsugi, T., Yamamuro, T., Nakamura, T., Four calcium phosphate ceramics as bone substitute for non-weight bearing (1993) Biomaterials, 14, pp. 216-221; Kitsugi, T., Yamamuro, T., Nakamura, T., Transmission electron microscopy observations at the interface of bone and four types of calcium phosphate ceramics with different calcium/phosphorus molar ratios (1995) Biomaterials, 16, pp. 1101-1107; Yu, B., Liang, K., Gu, S., (2002) J. Chin. Ceram. Soc., 30 (1), pp. 77-80; Kasuga, T., Sawada, M., Nogami, M., Biomaterials, bioactive ceramics prepared by sintering and crystallization of calcium phosphate invert glasses (1999) Biomaterials, 20, pp. 1415-1420; Zhang, Y., Santos, J.D., Microstructural characterization and in vitro apatite formation of CaO-P 2O 5-TiO 2MgO-Na 2O glass-ceramics (2001) J. Eur. Ceram. Soc., 21, pp. 169-175; Kokubo, T., Ito, S., Sakka, S., Formation of a high strength bioactive glass ceramic in the system MgO-CaO-SiO 2-P 2O 5 (1986) J. Mater. Sci., 21, pp. 536-540; Hosono, H., Zhang, Z., Abe, Y., Porous glass-ceramics in the CaO-TiO 2-P 2O 5 system (1989) J. Am. Ceram. Soc., 72, pp. 1587-1589; Zhang, Y., Santos, J.D., Crystallization and microstructure analysis of calcium phosphate-based glass ceramics for biomedical applications (2000) J. Non-Cryst. Solids, 272, pp. 14-21; Li, Y., Study on bioactive glass-ceramics in Na 2O-TiO 2-CaO-P 2O 5 system (2001), Chinese source, Dissertation, Hangzhou: Zhejiang UniversityKokubo, T., Surface chemistry of bioactive glass-ceramics (1990) J. Non.-Cryst. Solids, 120, pp. 138-151
Keywords: Bioactivity; Calcium Compounds; calcium phosphate; Crystalline materials; Crystalline phase; Crystallization; Glass ceramics; Glass-ceramics; Heat treatment; Nucleation; Phase separation; Phosphates

In vitro degradation studies of calcium phosphate glass ceramics prepared by controlled crystallization - Dias, A.G.; Lopes, M.A.; Gibson, I.R.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2003)
Calcium phosphate glass ceramics with incorporation of small additions of two nucleating agents, MgO and K 2O were prepared in the metaphosphate and pyrophosphate region, using an appropriate two-step heat treatment of controlled crystallization defined by differential thermal analysis results. Identification and quantification of crystalline phases precipitated from the calcium phosphate glass were performed using X-ray diffraction and Rietveld analysis. The β-Ca 2P 2O 7 (β-DCP), KCa(PO 3) 3, β-Ca(PO 3) 2 and Ca 4P 6O 19 phases were detected in the glass ceramics. In order to evaluate the degradation of the glass ceramics prepared, degradation studies were carried out during 42 days in Tris-HCl solution at 37 °C, pH 7.4, using granules in the range of 355-415 μm. The materials presented a weight loss ranging up to 12%. The ions leached during the immersion mainly originated from the KCa(PO 3) 3 phase, probably due to the presence of K + ion in the calcium metaphosphate, and the residual glassy phase. The structural changes at the surface of materials during degradation have been analyzed by Fourier transform infrared spectroscopy and X-ray diffraction. Results showed that significant surface changes occurred with immersion time, with the decrease of KCa(PO 3) 3, β-Ca 2P 2O 7 and β-Ca(PO 3) 2 phases occurring at different periods of immersion. This study has demonstrated an easy way to prepared calcium phosphate materials with specific calcium phosphate phases and crystallization, and therefore specific degradation rates. © 2003 Elsevier B.V. All rights reserved.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JNCSBdoi: 10.1016/j.jnoncrysol.2003.08.056Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Depto. de Engenharia Metalurgica, Fac. de Engenharia da Univ. do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Hall, B.K., (1992) Bone, Fracture Repair and Regeneration, 5. , CRC;Vidal, J., Dossa, J., Le Tissu Osseux (1990) Collection: Biologie de l'Appareil Locomoteur, , L. Teot (Ed.); Legeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, , H.M. Meyers, N.Y. Karger (Eds.); Yamamuro, T., Hench, L.L., Wilson, J., Handbook of Bioactive Ceramics (1990) Bioactive Glasses and Glass Ceramics, 1. , Takao (Ed.), CRC; Hench, L.L., Wilson, J., Wilson, J., Handbook of Bioactive Ceramics (1990) Calcium Phosphate and Hydroxyapatite Ceramics, 2. , Yamamuro T. (Ed.), CRC; Kitsugi, T., Yamamuro, T., Nakamura, T., Oka, M., (1995) Biomaterials, 16, p. 1101; Kasuga, T., Abe, Y., (1999) J. Non-Cryst. Solids, 243, p. 70; Zhang, Y., Santos, J.D., (2000) J. Non-Cryst. Solids, 272, p. 14; Hartmann, P., Vogel, J., Schnabel, B., (1994) J. Non-Cryst. Solids, 176, p. 157; Brow, R.K., (2000) J. Non-Cryst. Solids, 263-264, p. 1; Jones, A.R., Winter, R., Greaves, G.N., Smith, I.H., (2001) J. Non-Cryst. Solids, 293-295, p. 87; Clément, J., Manero, J.M., Planell, J.A., Avila, G., Martínez, S., (1999) J. Mater. Sci.: Mater. Med., 10, p. 729; Zhang, Y., Lopes, M.A., Santos, J.D., (2001) Key Eng. Mater., 192-195, p. 643; Uo, M., Mizuno, M., Kuboki, Y., Makishima, A., Watari, F., (1998) Biomaterials, 19, p. 2277; Franks, K., Abrahams, I., Knowles, J.C., (2000) J. Mater. Sci.: Mater. Med., 11, p. 609; Kasuga, T., Abe, Y., (1998) J. Mater. Res., 13 (12), p. 3357; Franks, K., Abrahams, I., Georgiou, G., Knowles, J.C., (2001) Biomaterials, 22, p. 497; Hill, R.J., Howard, C.J., (1987) J. Appl. Crystallogr., 20, p. 467; Nyquist, R.A., (1997) Handbook of Infrared and Raman Spectra of Inorganic Compounds and Organics Salts (a4 - Volume Set), , Academic Press; Nan, Y., Lee, W.E., James, P.F., (1992) J. Am. Ceram. Soc., 75 (6), p. 1641; Reaney, I.M., James, P.F., Lee, W.E., (1996) J. Am. Ceram. Soc., 79 (7), p. 1934; Shi, W., James, P.F., (1991) Proceedings of a Conference on Physics of Non-crystalline Solids, , University of Cambridge, UK; Kasuga, T., Abe, Y., (1988) Proceedings of the XVIII International Congress on Glass, p. 31. , American Ceramic Society; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., (2002) Key Eng. Mater., 218-220, p. 149
Keywords: Calcium Compounds; Crystallization; Degradation; Differential thermal analysis; Fourier transform infrared spectroscopy; Glass ceramics; Heat treatment; Nucleating agents; Nucleation; X ray diffraction

Optimal detection of symmetry axis in digital chest X-ray images - Vinhais, C.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2003)
We present a method for detecting the axis of bilateral symmetry in a digital chest X-ray image and subsequently measuring the degree of symmetry of the image. The detection is achieved by analysing rotated-reflected digital chest X-ray images and it is posed as a global optimization problem solved with a probabilistic genetic algorithm (PGA). The global search is initially based on natural peak orientation information related to the orientation of the symmetry axis. Only a few generations of the PGA are needed to achieve convergence to all the images in the database. This method is applied directly on the intensity input image and does not require any prior segmentation. © Springer-Verlag Berlin Heidelberg 2003.
Keywords: image processing; Probabilistic genetic algorithm; Reflectional Symmetry

A probabilistic model for the cooperative modular neural network - Alexandre, L.A.; Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2003)
This paper presents a model for the probability of correct classification for the Cooperative Modular Neural Network (CMNN). The model enables the estimation of the performance of the CMNN using parameters obtained from the data set. The performance estimates for the experiments presented are quite accurate (less than 1% relative difference). We compare the CMNN with a multi-layer perceptron with equal number of weights and conclude that the CMNN is preferred for complex problems. We also investigate the error introduced by one of the CMNN voting strategies. © Springer-Verlag Berlin Heidelberg 2003.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; Departamento de Informática, Universidade da Beira Interior, Covilhã, Portugal; email: lfbaa@di.ubi.ptReferences: Auda, G., Kamel, M., Modular neural network classifiers: A comparative study (1998) J. Intel. Robotic Systems, pp. 117-129;De Bollivier, M., Gallinari, P., Thiria, S., Cooperation of neural nets and task decomposition (1991) Int. Joint Conf. on Neural Networks, 2, pp. 573-576. , Seattle, USA; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, pp. 79-87; Jacobs, R., Peng, F., Tanner, M., A bayesian approach to model selection in hierarchical mixtures-of-experts architectures (1997) Neural Networks, 10, pp. 231-241; Wanas, N., Kamel, M., Auda, G., Karray, F., Feature-based decision aggregation in modular neural network classifiers (1999) Pattern Recognition Letters, 20, pp. 1353-1359; Alexandre, L., Campilho, A., Kamel, M., Combining independent and unbiased classifiers using weighted average (2000) Proceedings of the 15th International Conference on Pattern Recognition, 2, pp. 495-498. , Barcelona, Spain, IEEE Press; Alexandre, L., Campilho, A., Kamel, M., On combining classifiers using sum and product rules (2001) Pattern Recognition Letters, 22, pp. 1283-1289; Kittler, J., Hatef, M., Duin, R., Matas, J., On combining classifiers (1998) IEEE Trans. PAMI, 20, pp. 226-239; Auda, G., Kamel, M., CMNN: Cooperative modular neural networks for pattern recognition (1997) Pattern Recognition Letters, 18, pp. 1391-1398; Auda, G., Kamel, M., Raafat, H., Voting schemes for cooperative neural network classifiers (1995) IEEE Int. Conference on Neural Networks, 3, pp. 1240-1243. , Australia

Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers - Martins, M.C.L.; Ratner, B.D.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2003)
The effect of surface composition and wettability on the adsorption of human serum albumin (HSA) was studied. Self-assembled monolayers (SAMs) containing mixtures of longer chain methyl- and shorter chain hydroxyl-terminated alkanethiols on gold were used to produce a range of surfaces with different wettabilities and exposed functional groups. Different SAMs were characterized by X-ray photoelectron spectroscopy, water contact angles, and Fourier transform infrared reflection absorption spectroscopy (IRAS). HSA adsorption onto the different SAMs was evaluated by contact angle measurements (wetting tension determinations), radiolabeling of proteins, and IRAS. Concerning HSA adsorption, all the techniques demonstrated higher HSA adsorption on more hydrophobic surfaces. The wetting tension measurements and IRAS suggested a gradual decrease of the HSA adsorption with increases of surface hydrophilicity. Radiolabeled albumin measurements also demonstrated a significant decrease of HSA adsorption on the pure hydroxyl-terminated SAMs. However, no significant differences were detected between mixed and pure methyl-terminated SAMs. Studies of HSA exchangeability with human fibrinogen have suggested that an ideal percentage of hydroxyl groups on the surface may increase albumin affinity without fibrinogen adsorption. © 2003 Wiley Periodicals, Inc.
Cited By (since 1996): 63Export Date: 21 November 2012Source: ScopusCODEN: JBMRCPubMed ID: 14517873Language of Original Document: EnglishCorrespondence Address: Martins, M.C.L.; INEB-Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cmartins@ibmc.up.ptChemicals/CAS: human serum albumin, 9048-49-1; thiol derivative, 13940-21-1; Biocompatible Materials; Gold, 7440-57-5; Proteins; Sulfhydryl CompoundsReferences: Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, J.L., (1996) Biomaterials Science - An Introduction to Materials in Medicine, , San Diego, CA: Academic;Kottke-Marchant, K., Anderson, J.M., Umemura, Y., Marchant, R.E., Effect of albumin coating on the in vitro blood compatibility of Dacron arterial prostheses (1989) Biomaterials, 10, pp. 147-155; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Kamath, K.R., Park, K., Surface modification of polymeric biomaterials by albumin grafting using γγρ;-radiation (1994) J Appl Biomater, 5, pp. 163-173; McFarland, C.D., Filippis, C.D., Jenkins, M., Tunstell, A., Rhodes, N.P., Williams, D.F., Steele, J.G., Albumin binding surfaces: In vitro activitv (1998) J Biomater Sci Polym Ed, 9, pp. 1277-1239; Ji, J., Feng, L., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin (2001) Biomaterials, 22, pp. 3015-3023; McFarland, C.D., Jenkins, M., Griesser, H.J., Chatelier, R.C., Steele, J.G., Underwood, P.A., Albumin binding surfaces: Synthesis and characterization (1998) J Biomater Sci Polym Ed, 9, pp. 1207-1225; Keogh, J.R., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 121, pp. 537-545; Tsai, C.C., Huo, H.H., Kulkarni, P., Eberhart, R.C., Biocompatible coatings with high albumin affinity (1990) ASAIO Trans, 36, pp. M307-M310; Bekos, E.J., Ranieri, J.P., Aebisher, P., Gardella Jr., J.A., Bright, F.V., Structural changes of bovine serum albumin upon adsorption to modified fluoropolymer substrates used for neural cell attachment studies (1995) Langmuir, 11, pp. 984-989; Bailly, A., Laurent, A., Lu, H., Elalami, I., Jacob, P., Mundler, O., Merland, J., Soria, C., Fibrinogen binding and platelet retention: Relationship with the thrombogenicity of catheters (1996) J Biomed Mater Res, 30, pp. 101-108; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers to understand the interactions of man-made surfaces with proteins and cells (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-78; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Endothelial cell growth and protein adsorption on terminal functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Ulman, A., (1991) An Introduction to Ultrathin Organic Films: From Langmuir-blodgett to Self-assembled, , San Diego, CA: Academic; Lestelius, M., (1996) Tailor-made Monolayer Assemblies for in Vitro Studies of Blood Protein-surface Interactions, , PhD Thesis. Linköping University, Sweden; Kalltorp, M., Carlén, A., Thomsen, P., Olsson, J., Tengvall, P., Analysis of rat plasma proteins desorbed from gold and methyl- and hydroxyl-terminated alkane thiols on gold surfaces (2000) J Mater Sci Mater Med, 11, pp. 191-199; Tengvall, P., Lundstrom, I., Liedberg, B., Protein adsorption studies on model organic surfaces: An ellipsometric and infrared spectroscopic approach (1998) Biomaterials, 19, pp. 407-422; Sigal, G.B., Mrksich, M., Whitesides, G.M., Effect of surface wettability on the adsorption of proteins and detergents (1998) J Am Chem Soc, 120, pp. 3464-3473; López, G.P., Biebuyck, H.A., Harter, R., Kumar, A., Whitesides, G.M., Fabrication and imaging of two-dimensional patterns of proteins adsorbed on self-assembled monolayers by scanning electron microscopy (1993) J Am Chem Soc, 115, pp. 10774-10781; Silin, V., Weetall, H., Vanderah, D., SPR studies of the nonspecific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interface Sci, 185, pp. 94-103; Bain, C.D., Whitesides, G.M., Formation of monolayers by the coadsorption of thiols on gold: Variation in the length of the alkyl chain (1989) J Am Chem Soc, 111, pp. 7164-7175; Bain, C.D., Evall, J., Whitesides, G.M., Formation of monolayer coadsorption of thiols on gold: Variation in the head group, tail group and solvent (1989) J Am Chem Soc, 111, pp. 7155-7164; Bain, C.D., Whitesides, G.M., Correlations between wettability and structure in monolayers of alkanethiols adsorbed on gold (1988) J Am Chem Soc, 110, pp. 3665-3666; Folkers, J.P., Laibirds, P.E., Whitesides, G.M., Self-assembled monolayers of alkanethiols on gold: Comparisons of monolayers containing mixtures of short- and long-chain constituents with CH 3 and CH 2OH terminal groups (1992) Langmuir, 8, pp. 1330-1341; Atre, S.V., Liedberg, B., Allara, D.L., Chain length dependence of the structure and wetting properties in binary composition monolayers of OH- and CH 3-terminated alkanethiolates on gold (1995) Langmuir, 11, pp. 3882-3893; Pan, S., Belu, A.M., Ratner, B.D., Self assembly of 16-mercapto-1-hexandecanol on gold: Surface characterization and kinetics (1997) Mat Sci Eng, C7, pp. 51-58; Adamson, A.W., Gast, A.P., (1997) Physical Chemistry of Surfaces, , New York: Wiley; Vogler, E.A., (1993) Interfacial Chemistry in Biomaterials Science. Surfactant Science, Series 49, pp. 183-250. , Beng JC, editor. New York: Marcel Dekker; Miller, R., Treppo, S., Voight, A., Zingg, W., Neumann, A.W., Contact angle kinetics of human albumin solutions at solid surfaces (1993) Colloids Surf, 69, pp. 203-208; Van Der Vegt, W., Van Der Mei, H.C., Busscher, H.J., Interfacial free energies in protein solution droplets on FEP-teflon by axisymmetric drop shape analysis by profile-IgG versus BSA (1993) J Colloid Interface Sci, 156, pp. 129-136; Serro, A.P.V., Fernandes, A.C., Saramago, B.J.V., Dynamic interfacial behaviour of bovine serum albumin solutions on titanium surfaces (1997) Colloid Surf A, 125, pp. 209-219; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of Biocompatibility Tests, 2, pp. 183-214. , Williams DF, editor. Boca Raton, FL: CRC Press; Du, Y.J., Cornelius, R.M., Brash, J.L., Measurement of protein adsorption to gold surface by radioiodination methods: Suppression of free iodide sorption (2000) Colloid Surf B, 17, pp. 59-67; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Feng, L., Andrade, J.D., Protein adsorption on low temperature isotropic carbon. III. Isoterms, competitivity, desorption and exchange of human albumin and fibrinogen (1994) Biomaterials, 15, pp. 323-333; Lima, J., Sousa, S.R., Ferreira, A., Barbosa, M.A., Interactions between calcium, phosphate, and albumin on the surface of titanium (2001) J Biomed Mater Res, 55, pp. 45-53; (1993) Iodine-125. A Guide to Radioiodination Techniques, p. 64. , Little Chalfont, England: Amersham Life Sciences, Amersham International, PLC; Ishida, T., Tsuneda, S., Nishida, N., Hara, M., Sasabe, H., Knoll, W., Surface-conditioning effect of gold substrates on octadecanethiol self-assembled monolayer growth (1997) Langmuir, 13, pp. 4638-4643; Smith, T., The hydrophilic nature of a clean gold surface (1980) J Colloid Interface Sci, 75, pp. 51-55; Castner, D.G., Hinds, K., Grainger, D.W., X-ray photoelectron spectroscopy sulfur 2p study of organic thiol and disulfide binding interactions with gold surfaces (1996) Langmuir, 12, pp. 5083-5086; Porter, M.D., Bright, T.B., Allara, D.L., Chidsey, C.E.D., Spontaneously organized molecular assemblies. 4. Structural characterization of n-alkyl thiol monolayers on gold by optical ellipsometry, infrared spectroscopy and electrochemistry (1987) J Am Chem Soc, 109, pp. 3559-3568; Nuzzo, R.G., Dubois, L.H., Allara, D.L., Fundamental studies of microscopic wetting on organic surfaces. Formation and structural characterization of a self consistent series of polyfunctional organic monolayers (1990) J Am Chem Soc, 112, pp. 558-569; Chidsey, C.E.D., Loiacono, D.N., Chemical functionality in self-assembled monolayers: Structural and electrochemical properties (1990) Langmuir, 6, pp. 682-691; Roeges, N.P.G., (1994) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , Chichester, England: John Wiley & Sons, Inc; Van Dulm, P., Norde, W., The adsorption of human plasma albumin on solid surfaces, with special attention to the kinetic aspects (1983) J Colloid Interface Sci, 91, pp. 248-255; Lee, J.H., Kim, H.W., Pak, P.K., Kim, S.S., Lee, H.B., Protein behaviour on polymer surfaces with hydrophilic functional groups (1994) Korea Polym J, 2, pp. 32-39; Peters, T., Serum albumin (1985) Adv Protein Chem, 37, pp. 161-240; Prime, K.L., Whitesides, G.M., Self-assembled organic monolayers: Model systems for studying adsorption of proteins at surfaces (1991) Science, 252, pp. 1164-1167; Malmsten, M., Lassen, B., Competitive adsorption at hydrophobic surfaces from binary protein systems (1994) J Colloid Interface Sci, 166, pp. 490-498; Petrash, S., Cregger, T., Zhao, B., Pokidysheva, E., Foster, M.D., Brittain, W.J., Sevastianov, V., Majkrzak, C.F., Changes in protein adsorption on self-assembled monolayers with monolayer order: Comparison of human serum albumin and human gamma globulin (2001) Langmuir-on Line, A, pp. G; Kurrat, R., Prenosil, J.E., Ramsden, J.J., Kinetics of human and bovine serum albumin adsorption at silica-titania surfaces (1997) J Colloid Interface Sci, 185, pp. 1-8; Andrade, J.D., Hlady, V., Protein adsorption and materials biocompatibility: A tutorial review and suggested hypotheses (1986) Advances Polymer Science, , Dusek K, editor. Heidelberg: Springer-Verlag
Keywords: Absorption spectroscopy; Adsorption; article; Biocompatible Materials; Contact angle; Contact angles; fourier transform infrared reflection absorption spectroscopy; Fourier transform infrared spectroscopy; Functional groups; gold; human serum albumin; hydrophilicity; hydrophobicity; IRAS; isotope labeling; measurement; Mixtures; monolayer culture; Monolayers; Protein adsorption; Proteins; Self-assembled monolayers; Spectrum Analysis; Sulfhydryl Compounds; surface property; tension; thiol derivative; Time Factors; wettability; X ray photoelectron spectroscopy; XPS

Surface engineering of poly(DL-lactide) via electrostatic self-assembly of extracellular matrix-like molecules - Zhu, H.; Ji, J.; Tan, Q.; Barbosa, M.A.; Shen, J. (BiomacromoleculesBiomacromolecules, 2003)
We report the development of new biomacromolecule coatings on biodegradable biomaterials based on electrostatic assembly of extracellular matrix-like molecules. Poly(ethylene imine) (PEI) was employed to engineer poly(DL-lactide) (PDL-LA) substrate to obtain a stable positively charged surface. An extracellular matrix- (ECM-) like biomacromolecule, gelatin, was selected as the polyelectrolyte to deposit on the activated PDL-LA substrate via the electrostatic assemble technique. The extracellular matrix-like multilayer on the PDL-LA substrate was investigated by attenuated total reflection (ATR-FTIR), X-ray photoelectron spectrscopy (XPS), contact angle, and atomic force microscopy (AFM). The gradual buildup of the protein layer was investigated by UV-vis spectra, and it was further given a quantitative analysis of the protein layer on the PDL-LA substrate via the radioiodination technique. The stability of the protein layer under aqueous condition was also tested by the radiolabeling method. Chondrocyte was selected as the model system for testing the cell behavior and morphology on modified PDL-LA substrates. The chondrocyte test about cell attachment, proliferation, cell activity and cell morphology by SEM, and confocal laser scanning microscopy (CLSM) investigation on extracellular matrix-like multilayer modified PDL-LA substrate was shown to promote chondrocyte attachment and growth. Comparing conventional coating methods, polyelectrolyte multiplayers are easy and stable to prepare. It may be a good choice for the modification of 3-D scaffolds used in tissue engineering. These very flexible systems allow broad medical applications for drug delivery and tissue engineering.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm025773pPubMed ID: 12625735Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science/Eng., Zhejing University, Hangzhou 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: gelatin, 9000-70-8; polyethyleneimine, 74913-72-7; polylactide, 26680-10-4; poly(lactide), 26969-66-4; PolyestersTradenames: AXIOVERT 200, Zeiss; ESCA LAB 200A, VG; Radiance 2100, Biorad; Shimadzu UV-1201, Shimadzu; SPA 400, Seiko; Vectro 22, BrukerManufacturers: Biorad; Bruker; Seiko; Shimadzu; VG; ZeissReferences: Sittinger, M., Perka, C., Schutz, O., Haupl, T., Burmester, G.R.Z., (1999) Rheumatol., 58, pp. 130-135;Kim, B.S., Mooney, D.J., (1998) Trends Biotechnol., 16, p. 224; Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., (2000) Macromol. Rapid Commun., 21, p. 319; Ulman, A., (1996) Chem. Rev., 96, p. 1533; Sano, M., Lvov, Y., Kunitake, T., (1996) Annu. Rev. Mater. Sci., 26, pp. 153-187; Laschewsky, A., (1997) Eur. Chem. Chronicle ECC, 2, pp. 13-24; Chluba, J., Voegel, J.C., Decher, G., Erbacher, P., Schaaf, P., Ogier, J., (2001) Biomacromolecules., 2, pp. 800-805; Iler, R., (1966) J. Colloid Interface Sci., 21, p. 569; Fromhertz, P., (1980) Electron Microscopy at Molecular Dimension, p. 338. , Baumeister, W., Ed.; Springer-Verlag: Berlin; Lee, H., Kepley, L., Hong, H.-G., Mallouk, T., (1988) J. Am. Chem. Soc., 110, p. 618; Decher, G., Hong, J.-D., (1991) Ber. Bunsen-Ges., 95, p. 1430; Decher, G., (1997) Science, 227, p. 1232; Lvov, Y., Decher, G., Mohwald, H., (1993) Langmuir, 9, p. 481; Lvov, Y., Haas, H., Decher, G., Mohwald, H., Mikhailov, A., Mtchedlishvily, B., Morgunova, E., Vainshtein, B., (1994) Langmuir, 10, p. 4232; Kleinfeld, E., Ferguson, G., (1994) Science, 265, p. 370; Hong, J.-D., Lowack, K., Schmitt, J., Decher, G., (1993) Prog. Colloid Polym. Sci., 93, p. 98; Schmitt, J., Grunewald, T., Krajer, K., Pershan, P., Decher, G., Loshe, M., (1993) Macromolecules, 26, p. 7058; Korneev, D., Lvov, Y., Decher, G., Schmitt, J., Yarodaikin, S., (1995) Physica B, 214, p. 954; Iodine-125, a Guide to Radioiodination Techniques (1993), p. 64. , Amersham Life ScienceHwan, M.K., Sang, B.H., Moon, S.K., Jong, S.K., Goo, T.O., Dong, H.H., (1996) J. Pharmacol. Toxicol. Methods, 36, pp. 163-169; Adamson, A.W., Gast, A.P., (1997) Physical Chemsitry of Surfaces, pp. 27-28. , John Wiley & Sons: New York; Klagsbrum, M., (1979) Methods Enzymol., 58, p. 560; Blum, R.N., Wright, R.A., (1992) J. Gen. Intern. Med., 7, pp. 140-144; Okuda, M., Miura, I., Juji, F., Takashima, H., (1994) Int. Arch. Allergy Immunol., 104 (1 SUPPL. 1), pp. 6-8; Mosmann, T., (1983) J. Immunol. Methods, 65, pp. 55-63; Zund, G., Ye, Q., Hoerstrup, S.P., Schoeberlein, A., Schmid, A.C., Grunenfelder, J., Vogt, P., Turina, M., (1999) Eur. J. Cardio-thoracic Surg., 15, pp. 519-524; Risbud, M.V., Bhonde, M.R., Bhonde, R.R., (2001) J. Biomed. Mater. Res., 57, pp. 300-305; Strand, B.L., Ryan, T.L., In't Veld, P., Kulseng, B., Rokstad, A.M., Skjak-Brek, G., Espevik, T., (2001) Cell Transplant., 10, pp. 263-275; De Ceuninck, F., Gaufillier, S., Bonnaud, A., Sabatini, M., Lesur, C., Pastoureau, P., (2001) Biochem. Biophys. Res. Commun., 285, pp. 926-931; Bancel, S., Hu, W.S., (1996) Biotechnol. Prog., 12, pp. 398-402; Davids, S., (1993) Test Procedures for the Blood Compatibility of Biomaterials, pp. 287-330. , Kluwer Academic Publishers: Dordrecht
Keywords: animal cell; Animalia; Animals; article; Atomic force microscopy; biodegradability; biomaterial; cartilage cell; cell activity; cell adhesion; cell function; cell growth; cell proliferation; cell structure; Cells, Cultured; Chondrocytes; confocal laser microscopy; controlled study; Electron Probe Microanalysis; Electrostatics; extracellular matrix; Fourier transform infrared spectroscopy; gelatin; macromolecule; Macromolecules; Microscopy, Atomic Force; nonhuman; polyelectrolyte; Polyesters; Polyethyleneimine; Polyethylenes; polylactide; priority journal; protein analysis; protein stability; quantitative analysis; Rabbits; radioiodination; Scanning electron microscopy; Self assembly; Spectrophotometry, Ultraviolet; Spectroscopy, Fourier Transform Infrared; Surface charge; Surface engineering; Surface Properties; Tissue engineering; Ultraviolet spectroscopy; X ray photoelectron spectroscopy

Synthesis of hydroxyapatite and tricalcium phosphate nanoparticles - Preliminary studies - Manuel, C.M.; Ferraz, M.P.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2003)
The wet mechanochemical process (MC) and chemical precipitation (CP) used to prepare hydroxyapatite (HA) and tricalcium phosphate (TCP) nanoparticles proved to be successful. In mechanochemical treatment, water and ethanol were used as a solvent but the last one improved particles agglomeration and decreased HA formation. This effect was also observed when aging temperature was decreased in wet chemical precipitation.
Conference code: 60907Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Manuel, C.M.; Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: candida@ibmc.up.ptReferences: Rhee, S.-H., (2002) Biomaterials, 23, pp. 1147-1152;Yeong, K.C.B., Wang, J., Ng, S.C., (2001) Biomaterials, 22, pp. 2705-2712; Fowler, B.O., Moreno, E.C., Brown, W.E., (1966) Arch. Oral Biol., 11, pp. 477-492
Keywords: Agglomeration; Calcium Compounds; Chemical precipitation; hydroxyapatite; Mechanochemical treatment; nanoparticles; Nanostructured materials; Precipitation (chemical); Synthesis (chemical); Tricalcium phosphate

The use of geographic information systems in health data analysis - De Pina, M.D.F. (O uso dos sistemas de informação geográfica na análise de dados de saúdeArquivos de MedicinaArq. Med., 2003)
Keywords: article; data analysis; geographic distribution; geographic information system; health survey; information system; Statistical analysis

Cellulose phosphates as biomaterials. In vivo biocompatibility studies - Fricain, J.C.; Granja, P.L.; Barbosa, M.A.; De Jéso, B.; Barthe, N.; Baquey, C. (BiomaterialsBiomaterials, 2002)
Femoral implantation of regenerated cellulose hydrogels revealed their biocompatibility, but a complete osseointegration could not be observed. Phosphorylation was therefore envisaged as the means to enhance cellulose bioactivity. In vitro studies showed that regenerated cellulose hydrogels promote bone cells attachment and proliferation but do not mineralize in acellular simulated physiological conditions. On the contrary, phosphorylated cellulose has shown an opposite behavior, by inducing the formation of a calcium phosphate layer in simulated physiological conditions, but behaving as a poor substrate for bone cells attachment and proliferation. In order to investigate the in vivo behavior of these materials, and assess the influence of mineralization induction ability vs. bone cells compatibility, unmodified and phosphorylated cellulose hydrogels were implanted in rabbits for a maximum period of 6 months and bone regeneration was investigated. Despite the difficulties arising from the retraction of cellulose hydrogels upon dehydration during the preparation of retrieved implants, histological observations showed no inflammatory response after implantation, with bone intra-spongious regeneration of cells and the integration of the unmodified as well as the phosphorylated cellulose implants. After a maximum implantation period of 6 months, histological observations, histomorphometry and the measurement of the amount of 45Ca incorporated in the surrounding tissue indicated a slightly better osseointegration of phosphorylated cellulose, although no significant differences between the two materials were found. © 2001 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 45Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00152-1PubMed ID: 11791931Language of Original Document: EnglishCorrespondence Address: Granja, P.L.; Laboratório de Biomateriais, INEB-Inst. de Engenliaria Biomedica, Rua do Campo Alegre, 823-4150-180 Porto, Portugal; email: pgranja@ibmc.up.ptChemicals/CAS: Biocompatible Materials; Calcium Radioisotopes; Calcium, 7440-70-2; Cellulose, 9004-34-6; phosphocellulose, 9015-14-9References: Jochanan, H., Boss, M.D., Osseointegration (1999) J Long-Term Eff Med Impl, 9, pp. 1-10;Albrektsson, T., Hard tissue response (1998) Handbook of biomaterial properties, pp. 500-512. , Black J, Hastings G, editors. London, UK: Chapman & Hall; Hench, L.L., Bioactive materials: The potential for tissue regeneration (1998) J Biomed Mater Res, 41, pp. 511-517; Yaszemski, M.J., Payne, R.G., Hayes, W.C., Langer, R., Mikos, A.G., Evolution of bone transplantation: Molecular, cellular and tissue strategies to engineer human bone (1996) Biomaterials, 17, pp. 175-185; Hollinger, J., McAllister, B., Bone and its repair (1995) Bioceramics, 8, pp. 3-9. , Wilson J, Hench LL, Greenspon D, editors. FL, USA: Pergamon Press; Friedman, R.J., Black, J., Galante, J.O., Jacobs, J.J., Skinner, H.B., Current concepts in orthopaedic biomaterials and implant fixation (1993) J Bone Jt Surg, 75 A, pp. 1086-1109; Bakker, D., Grote, J.J., Vrouenraets, C.M.F., Hesseling, S.C., De Wijn, J.R., Van Blitterswijk, C.A., Bone-bonding polymer (polyactive™) (1990) Clinical implant materials, Advances in Biomaterials Series, 9, pp. 99-104. , Heimke G, Soltész U, Lee AJC, editors. Amsterdam, The Netherlands: Elsevier; LeGeros, R.Z., Calcium phosphate materials in restorative dentistry: A review (1988) Adv Dent Res, 2, pp. 164-183; Hastings, G.W., Mahmud, F.A., Intelligent orthopaedic materials (1993) J Intell Mat Syst Str, 4, pp. 452-456; Black, J., (1988) Orthopaedic biomaterials in research and practice, , New York, USA: Churchill Livingstone; Li, P., Ye, X., Kangasniemi, I., De Blieck-Hogervorst, J.M.A., Klein, C.P.A.T., De Groot, K., In vivo calcium phosphate formation induced by sol-gel-prepared silica (1995) J Biomed Mater Res, 29, pp. 325-328; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., Apatite coated on organic polymers by biomimetic process: Improvement in its adhesion to substrate by glow-discharge treatment (1995) J Biomed Mater Res, 29, pp. 349-357; Li, P., Ohtsuki, T., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., Process of formation of bone-like apatite layer on silica gel (1993) J Mater Sci: Mater Med, 4, pp. 127-131; Radin, S.R., Ducheyne, P., The effect of calcium phosphate ceramic composition and structure on in vitro behavior. II. Precipitation (1993) J Biomed Mater Res, 27, pp. 35-45; Puleo, D.A., Nanci, A., Understanding and controlling the bone-implant interface (1999) Biomaterials, 20, pp. 2311-2321; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., Attachment of cultured human bone cells to novel polymers (1999) J Biomed Mater Res, 44, pp. 1-11; Dalton, B.A., McFarland, C.D., Gengenbach, T.R., Griesser, H.J., Steele, J.G., Polymer surface chemistry and bone cell migration (1998) J Biomater Sci Polym Ed, 9, pp. 781-799; Scotchford, C.A., Cooper, E., Leggett, G.J., Downes, S., Growth of human osteoblast-like cells on alkenethiol on gold self-assembled monolayers: The effect of surface chemistry (1998) J Biomed Mater Res, 41, pp. 431-442; Adams, A.M., Soames, J.V., Searle, R.F., Ultrastructural changes in cultured human periodontal ligaments cells exposed to dental materials (1995) J Biomed Mater Res, 29, pp. 999-1004; Lamba, N.M.K., Baumgartner, J.A., Cooper, S.L., Cell-synthetic surface interactions (1998) Frontiers in tissue engineering, pp. 121-137. , Patrick CW, Mikos AG, McIntire LV, editors. Amsterdam, The Netherlands: Elsevier; Dalton, B.A., McFarland, C.D., Gengenbach, T.R., Griesser, H.J., Steele, J.G., Polymer surface chemistry and bone cell migration (1998) J Biomater Sci Polym Ed, 9, pp. 781-799; Healy, K.E., Thomas, C.H., Rezania, A., Kim, J.E., McKeown, P.J., Lom, B., Hockberger, P.E., Kinetics of bone cell organization and mineralization on materials with patterned surface chemistry (1996) Biomaterials, 17, pp. 195-208; Kasemo, B., Lausmaa, J., Material-tissue interfaces: The role of surface properties and processes (1995) Environ Health Perspect, 102, pp. 41-45; Von Recum, A.F., Van Kooten, T.G., The influence of micro-topography on cellular response and the implications for silicone implants (1995) J Biomater Sci Polym Ed, 7, pp. 181-198; Vogler, E.A., (1993) Interfacial chemistry in biomaterials science, Surfactant Science Series, vol. 49 (Wettability), 49, pp. 183-250. , Berg JC, editor. New York, USA: Marcel Dekker; Horbett, T.A., Weathersby, P.K., Adsorption of proteins from plasma to a series of hydrophilic-hydrophobic copolymers. I. Analysis with the in situ radionation technique (1981) J Biomed Mater Res, 15, pp. 403-423; Martson, M., Viljanto, J., Hurme, T., Saukko, P., Biocompatibility of cellulose sponge with bone (1998) Eur Surg Res, 30, pp. 426-432; Gross, U., Muller-Mai, C., Voigt, C., The tissue response on cellulose cylinders after implantation in the distal femur of rabbits (1992) Fourth World Biomaterials Congress, p. 192. , Berlin, Germany, April; Chauveaux, D., Barbie, C., Barthe, X., Baquey, C., Poustis, J., Biological behaviour of cellulosic materials after bone implantation: Preliminary results (1990) Clin Mater, 5, pp. 251-258; Ikada, Y., Biomedical applications of cellulose membranes (1989) Cellulose: structural and functional aspects, pp. 447-455. , Kennedy JF, Phillips GO, Williams PA, editors. Chichester, UK: Ellis Horwood; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., Noishiki, Y., Tissue biocompatibility of cellulose and its derivatives (1989) J Biomed Mater Res, 23, pp. 125-133; Franz, G., Polysaccharides in pharmacy (1986) Adv Polym Sci, 76, pp. 1-30; Philipp, B., Bock, W., Schierbaum, F., Application of polysaccharides and their derivatives as supporting materials and auxiliary substances in medicine and nutrition (1979) J Polym Sci Polym Symp, 66, pp. 83-100; Galgut, P.N., Oxidized cellulose mesh. I. Biodegradable membrane in periodontal surgery (1990) Biomaterials, 11, pp. 561-564; Skoog, T., The use of periosteum and surgicel® for bone restoration in congenital clefts of the maxilla (1967) Scand J Plast Reconstr Surg, 1, pp. 113-130; Degenshein, G.A., Hurwitz, A., Ribacoff, S., Experience with regenerated oxidized cellulose (1963) NY State J Med, 63, pp. 2639-2643; Poustis, J., Baquey, C., Chauveaux, D., Mechanical properties of cellulose in orthopaedic devices and related environments (1994) Clin Mater, 16, pp. 119-124; Baquey, C., Barbié, C., More, N., Rouais, F., Poustis, J., Chauveaux, D., In vivo study of the biostability of a cellulose material (1992) Fourth World Biomaterials Congress, p. 365. , Berlin, Germany, April; Brie, J., Lafage, M.H., Chauveaux, D., Gueroult, J.M., Poustis, J., Baquey, C., La cellulose macroporeuse: Un matériau potentiellement utilisable pour le comblement osseux. Biomatériaux et organes artificiels (1992) Proceedings of the BIOMAT 92 Congress, , Bordeaux, France, November; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D., Biocompatible, hydrophilic material. Method of manufacture and uses of same, , Fr Pat No. 8610331, 1986; Eur Pat No. 0256906 A1, 1987; US Pat No. 4904258, 1990; Barbié, C., Chauveaux, D., Baquey, C., Poustis, J., Pommier, J.C., Morlier, R., Ducassou, D., Évaluation des proprietés mecaniques de matériaux cellulosiques et perspectives d'application originales de ces matériaux en chirurgie orthopédique (1987) Calcif Tiss Biomaterials, Proceedings of the BIOMAT 87 Congress, pp. 319-325. , Bordeaux, France, December; Li, S., Liu, Q., De Wijn, J., Wolke, J., Zhou, B., De Groot, K., In-vitro apatite formation on phosphorylated bamboo (1997) J Mater Sci: Mater Med, 8, pp. 543-549; Mucalo, M.R., Yokogawa, Y., Toryiama, M., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., Growth of calcium phosphate on surface-modified cotton (1995) J Mater Sci: Mater Med, 6, pp. 597-605; Mucalo, M.R., Yokogawa, Y., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., Further studies of calcium phosphate growth on phosphorylated cotton fibres (1995) J Mater Sci: Mater Med, 6, pp. 658-669; Granja, P.L., Baquey, C., Pouységu, L., Bareille, R., De Jéso, B., Barbosa, M.A., (1996) Cellulose-based biomaterials for bone regeneration: Hemi-synthesis and characterisation. Polymers in Medicine and Surgery - PIMS'96, pp. 73-80. , Glasgow, UK; Granja, P.L., Barbosa, M.A., Pouységu, L., De Jéso, B., Baquey, C., Cellulose phosphates as biomaterials (1999) Frontiers in biomedical polymers applications 2, pp. 195-225. , Lancaster, PA, USA: Technomic Press; Granja, P.L., Pouységu, L., De Jéso, B., Rouais, F., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Mineralization of chemically modified regenerated cellulose hydrogels (2001) J Mater Sci: Mater Med, , submitted for publication; Granja, P.L., De Jéso, B., Bareille, R., Rouais, F., Baquey, C., Barbosa, M.A., (2001) Cellulose phosphates as biomaterials. In vitro biocompatibility studies, , submitted for publication; (1994) Évaluation biologique des dispositifs médicaux. Partie 6: Essais concernant les effets locaux après implantation; Wolf, E., Roser, K., Hahn, M., Wezkerling, H., Delling, G.G., Enzyme and immunohistochemistry on undecalcified bone and bone marrow biopsy after embedding in plastic: A new embedding method for routine application (1992) Virchow Archiv Pathol Anat Histopathol, 420, pp. 17-24; Van der Lubbe, H.B.M., Patchin, C., De Groot, K., A simple method for preparing thin (10 μm) histological sections of undecalcified plastic embedded bone with implant (1988) Saint Technol, 63, pp. 171-176; Daculsi, G., LeGeros, R.Z., Nery, E., Lynch, K., Transformation of biphasic calcium phosphate ceramics in vivo (1989) J Biomed Mater Res, 23, pp. 883-894; Charpak, G., Dominik, W., Zaganidis, N., Optical imaging of the spatial distribution of b-particles emerging from surfaces (1989) Proc Natl Acad Sci USA, 86, pp. 1741-1745; Charpak, G., Dominik, W., Fabre, J.P., Gaudaen, J., Sauli, F., Suzuki, M., Studies of light emission by continuously sensitive avalanche chambers (1988) Nucl Instrum Methods A, 269, pp. 142-148; Charpak, G., Dominik, W., Fabre, J.P., Santiard, J.C., Sauli, F., Solomey, N., Gaseous detectors with parallel electrodes and anode mesh planes (1979) Nucl Instrum Meth, 161, pp. 19-34; Daculsi, G., Passutti, N., Effect of the macroporosity for the osseous substitution of calcium phosphate ceramics (1990) Biomaterials, 11, pp. 86-87; Le Huec, J.C., Clément, D., Brouillaud, B., Barthe, N., Dupuy, B., Foliguet, B., Basse-Cathalinat, B., Evolution of the local calcium content around irradiated β-tricalcium phosphate ceramic implants: In vivo study in the rabbit (1998) Biomaterials, 19, pp. 733-738; Bloebaum, D., Bachus, K., Momberger, N., Hofmann, A., Mineral apposition rates of human cancellous bone at the interface of porous coated implants (1994) J Biomed Mater Res, 28, pp. 537-544; Gross, U.M., Hard tissue histology (1999) Handbook of biomaterials evaluation: scientific, technical and clinical testing of implant materials. 2nd Ed., pp. 689-719. , von Recum AF, editor. MI, USA: Edwards Brothers, Ann Arbor Science; Sakkers, R.J.B., Dalmeyer, R.A.J., De Wijn, J.R., Van Blitterswijk, C.A., Use of bone-bonding hydrogel copolymers in bone: An in vitro and in vivo study of expanding PEO-PBT copolymers in goat femora (2000) J Biomed Mater Res, 49, pp. 312-318; Elliot, J.C., (1994) Structure and chemistry of the apatites and other calcium orthophosphates, Studies in Inorganic Chemistry Series, 18. , Amsterdam, The Netherlands: Elsevier; Aoki, H., (1994) Medical applications of hydroxyapatite, , Tokyo, Japan: Ishiyaku EuroAmerica; Goodman, S., Aspenberg, P., Effects of mechanical stimulation on the differentiation of hard tissues (1993) Biomaterials, 14, pp. 563-569; Klemm, D., Philipp, B., Heinze, T., Heinze, U., Wagenknecht, W., (1998) Comprehensive cellulose chemistry, vol. 2, functionalization of cellulose, 2, pp. 133-140. , Weinheim, Germany: Wiley-VCH Verlag. Chapter 4; Touey, G.P., Kingsport, T., Preparation of cellulose phosphates, , US Pat No. 2759924, 1956; Hayashi, T., Biodegradable polymers for biomedical uses (1994) Prog Polym Sci, 19, pp. 663-702; Fricain, J.C., Baquey, C., Dupuy, B., Resorption of corals implanted in diffusion chambers (1995) J Mater Sci: Mater Med, 6, pp. 680-684
Keywords: animal experiment; Animal implantation; animal tissue; Animalia; Animals; article; Biocompatibility; Biocompatible Materials; biomaterial; Biomaterials; Bone; bone cell; bone mineralization; Bone Regeneration; Calcium; calcium 45; Calcium Compounds; calcium phosphate; Calcium Radioisotopes; cell adhesion; cell proliferation; Cells; Cellulose; Cellulose phosphate; Chemical modification; controlled study; Dehydration; histology; hydrogel; Hydrogels; implant; in vivo study; Inflammation; materials testing; Microscopy, Electron, Scanning; morphometrics; nonhuman; Oryctolagus cuniculus; Osseointegration; Phosphates; Phosphorylation; priority journal; Prostheses and Implants; rabbit; Rabbits; Regenerated cellulose hydrogels

Densification route and mechanical properties of Si 3N 4-bioglass biocomposites - Amaral, M.; Lopes, M.A.; Silva, R.F.; Santos, J.D. (BiomaterialsBiomaterials, 2002)
The processing route and the final microstructural and mechanical characteristics of a novel biomaterial composite are described. This new material is composed of 70 wt% Si 3N 4 ceramic phase and 30 wt% bioglass, the later performing as a liquid sintering aid system and simultaneously providing bioactivity characteristics to the composite. The conditions for fabrication of an almost fully dense material (∼98% of relative density) were pursued. Optimised parameters were 1350°C-40min-30 MPa by hot-pressing technique. The very fast densification rate of the process avoided the crystallisation of the bioglass intergranular phase and therefore its intrinsic properties were maintained. Also, the large amount of glassy phase assured the densification by liquid phase assisted grain rearrangement without Si 3N 4 phase transformation. The final mechanical properties of the Si 3N 4-bioglass were as follows: fracture toughness, K IC = 4.4 MPa m 1/2; Vickers hardness, H V = 10.3 GPa; Young's modulus, E = 197 GPa; bending strength, σ R = 383 MPa; Weibull modulus, m = 8.3. These values provide an attractive set of properties among other bioactive materials, namely by upgrading the main drawback of bioceramics and bioglasses for high-load medical applications, which is the lack of satisfactory fracture toughness. © 2001 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00194-6PubMed ID: 11771704Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Secção de Materiais, Fac. Eng. da Univ. do Porto (FEUP), Universidade do Porto, Rua Roberto Frias, 4200-465 Porto Cedex, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Biocompatible Materials; Bioglass; Ceramics; Composite Resins; Silicon Compounds; silicon nitride, 12033-89-5Tradenames: BioglassReferences: Kue, R., Sohrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteacalcin production by human osteablast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201;Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride-Bioglass®45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Gazzara, C.P., Messier, D.R., Determination of phase content of Si 3N 4 by X-ray diffraction analysis (1997) Am Ceram Soc Bull, 56 (9), pp. 777-780; Niihara, K., Morena, R., Hasselman, D.P., Evaluation of K IC of brittle solids by the indentation method with low crack-to-indent ratios (1982) J Mater Sci Lett, 1, pp. 13-16; Standard test method for dynamic Young's modulus, shear modulus, and Poisson's ratio for advanced ceramics by impulse excitation of vibration; Kingery, W.D., Densification during sintering in the presence of a liquid phase. I. Theory (1959) J Appl Phys, 30 (3), pp. 301-306; Ziegler, G., Heinrich, J., Wötting, G., Review: Relationships between processing, microstructure and properties of dense and reaction-bonded silicon nitride (1987) J Mater Sci, 22, pp. 3041-3086; Filho, O.P., LaTorre, G.P., Hench, L.L., Effect of crystallization on apatite-layer formation of bioactive glass 45S5 (1996) J Biomed Mater Res, 30, pp. 509-514; Evans, A.G., Wilshaw, T.R., Quasi-static solid particle damage in brittle solids I. Observations, analysis and implications (1976) Acta Metall, 24, pp. 939-956; Yamamuro, T., Reconstruction of the iliac crest with bioactive glass-ceramic prostheses (1990) Handbook of Bioactive Ceramics, 1, pp. 335-342. , Yamamuro T, Hench LL, Wilson J, editors. Boca Raton: CRC Press; Hench, L.L., Bioceramics (1998) J Am Ceram Soc, 81, pp. 1705-1728; Ravaglioli, A., Krajewski, A., (1992) Bioceramics - materials, properties and applications, , London: Chapman & Hall; Kong, Y.M., Kim, S., Kim, H.E., Reinforcement of hydroxyapatite bioceramic by addition of ZrO 2 coated with Al 2O 3 (1999) J Am Ceram Soc, 82 (11), pp. 963-968; Ducheyne, P., Marcolongo, M., Schepers, E., Bioceramic composites (1993) An Introduction to Bioceramics. Advanced series in ceramics, 1, pp. 281-297. , Hench L, Wilson J, editors. Singapore: World Scientific. Chapter 15
Keywords: 3N; 4-bioglass composites; article; Bending strength; Biocompatible Materials; biomaterial; Biomaterial composites; Biomaterials; Ceramic materials; ceramics; Composite Resins; Crystallization; Densification; Densification behaviour; density; Elastic moduli; Fracture toughness; glass; hardness; heat; Hot pressing; Hot-pressing; Kinetics; Mechanical properties; phase transition; Phase transitions; priority journal; Si; Silicon compounds; silicon derivative; Sintering; strength; Stress, Mechanical; technique; Thermodynamics; Vickers hardness testing; X-Ray Diffraction; young modulus

Electrochemical and microstructural studies of tantalum and its oxide films for biomedical applications in endovascular surgery - Silva, R.A.; Walls, M.; Rondot, B.; Da Cunha Belo, M.; Guidoin, R. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
The most popular coronary stents are made of 316L stainless steel and self-expandable Nitinol. Nevertheless, Ta has already been used to make stents for endovascular surgery and may constitute a good alternative to the other materials because of its higher corrosion resistance and radio-opacity property, which may facilitate the follow-up of stent catheterization. The characterization of Ta and its natural passive oxide films has been performed in a 0.15M NaCl solution (simulated body fluid - SBF) using anodic polarizations, electrochemical impedance spectroscopy and photoelectrochemical techniques. Changes in microstructure have been observed by atomic force microscopy (AFM). Polarization curves show the existence of a current density increase between 1.40 and 1.80V. Bode complex plots show that some perturbation of the film occurred in this potential interval which may be associated with a decrease in polarization resistance, Rp, indicating that the film may be less resistant to corrosive attack. Mott-Schottky capacity measurements show that the density of donors, Nd, varies with polarization. The optical band gap, E g, which is equal to 4.1 eV did not show variations in our experiments. The localized formation on the electrode surface, in the above potential interval of a Ta compound (possibly an oxide-hydroxide) was observed by AFM, and this may explain the appearance of the current density peak and capacity behavior at those potentials. © 2002 Kluwer Academic Publishers.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1014779008598Language of Original Document: EnglishCorrespondence Address: Silva, R.A.; CIEA/ISEP, Rua S. Tomé, 4200 Porto, PortugalReferences: Sigwart, U., Puel, J., Mirkovitch, V., Joffre, F., Kappenberger, L., (1987) New Engl. J. Med., 316 (12), pp. 701-706;Serruys, P.W., De Jaegere, P., Kiemeneij, F., Macaya, C., Heindrickx, W., (1994) New Engl. J. Med., 331 (8), pp. 489-495; Fischman, D.L., Leon, M.B., Baim, D.S., Schatz, R.A., Savage, M.P., Penn, I., (1994) New Engl. J. Med., 331 (8), pp. 496-501; Serruys, P.W., Emanuelsson, H., Van Der Giessen, W., Lunn, A.C., Kiemeney, F., Macaya, C., (1996) Circulation, 93 (3), pp. 412-422; Cohen, D.J., Breall, J.A., Ho, K.K., Kuntz, R.E., Goldman, L., Baim, D.S., (1995) New Engl. J. Med., 92, pp. 1859-1874; Cohen, D.J., Breall, J.A., Ho, K.K., Weintraub, R.M., Kuntz, R.E., Weistein, M.C., (1993) J. Amer. Coll. Cardiology, 22 (4), pp. 1052-1059; Cohen, D.J., Krumholz, H.M., Sukin, C.A., Ho, K.K., Siegrist, R.B., Cleman, M., (1995) Circulation, 92, pp. 2480-2487; Colombo, A., Hall, P., Nakamura, S., Almagor, Y., Maiello, L., Martini, O., (1995) Circulation, 91 (6), pp. 1676-1688; Goy, J.J., Eeckhout, E., Stauffer, J.C., Vogt, P., Kappenberger, L., (1995) Catheter. Cardiov. Diag., 34, pp. 128-132; Hamasaki, N., Nosaka, H., Nobuyoshi, M., (1995) J. Amer. Coll. Cardiol., 239 A (SPEC. ISSUE); Hamm, C.W., Beythien, C., Sievert, H., Langer, A., (1995) Amer. Heart J., 129 (3), pp. 423-429; Kiemeneij, F., Hofland, J., Laarman, G.J., Hupkens Van der Elst, D., Van der Lubbe, H., (1995) Catheter. Cardiov. Diag., 35, pp. 301-308; Mehan, V.K., Kaufmann, U., Urban, P., Chatelain, P., Meier, B., (1995) Catheter. Cardiov. Diag., 34, pp. 122-127; Robinson, N.M., Thomas, M.R., Jewitt, D.E., Wainwright, R.J., (1995) Cardiology, 7 (6), pp. 156-164; Stauffer, J.C., Eeckhout, E., Goy, J.J., Nacht, C.A., Vogt, P., Kappenberger, C., (1995) J. Invas. Cardiol., 7 (8), pp. 221-227; Webb, J., Stertzer, S., Ahmad, T., Carere, R., Mercier, B., Dodek, A., (1996) Catheter. Cardiov. Diag., 37, pp. 120-124; Schöneberger, A.A., Schmidt, K., (1996) New Engl. J. Med., 335 (15), p. 1160; Priestley, K.A., Clague, J.R., Buller, N.P., Sigwart, U., (1996) Europ. Heart J., 17 (3), pp. 438-444; Silva, R.A., Marques, M.A., Silveira, A., Walls, M., Rondot, B., Guidoin, R., (1998) Proceedings of the 14th European Conference on Biomaterials, p. 37. , The Hague, September, edited by the Dutch Society for Biomaterials; Pypen, C.M.J.M., Plenk H., Jr., Ebel, M.F., Svagera, R., Verenisch, J., (1997) J. Mater. Sci. Mater. Med., 8, pp. 781-784; Park, J.B., (1984) Biomaterials Science and Engineering, p. 217. , New York, Plenum Press; Jonhson, P.F., Bernstein, J.J., Hunter, G., Dawson, W.W., Hench, L.L., (1977) J. Biomed. Mater. Res., 11, pp. 637-656; Black, J., (1994) Clin. Mater., 16, pp. 167-173; Stackpool, G.J., Kay, A.B., Morton, P., Harvey, E.J., Tanzer, M., Bone, J.D., (1995) Proceedings of Combined Orthopaedic Research Societies Meeting, p. 45. , edited by Orthopaedic Research Society (Rider Dickerson Inc., Chicago); Macagno, V.A., Schultze, J.W., (1984) J. Electroanal. Chem., 180, pp. 157-170; Schultze, J.W., Macagno, V.A., (1986) Electrochim. Acta, 31, pp. 355-363; Kerrec, O., Devilliers, D., Groult, H., Chemla, M., (1995) Electrochim. Acta, 40, pp. 719-724; Degryse, R., Gomes, W.P., Cardon, F., Vennik, J., (1975) J. Electrochem. Soc., 122, p. 711; Gartner, W.W., (1959) Phys. Rev., 116, p. 84; Butler, M.A., (1977) J. Appl. Phys., 48, p. 1914; Ginley, D.S., Butler, M.A., (1977) J. Appl. Phys., 48, p. 2019; Clechet, P., Martin, J.-R., Olier, R., Vallouy, C., (1976) C. R. Acad. Sci. Paris, 282, pp. 887-890; Lohrengel, M.M., (1994) Electrochim. Acta, 39, pp. 1265-1271
Keywords: article; Atomic force microscopy; body fluid; coronary stent; Corrosion; Corrosion resistance; Current density; Electric Potential; electrochemical analysis; Electrochemical impedance spectroscopy; electrochemistry; electrode; endovascular surgery; Energy gap; film; heart catheterization; hydroxide; Materials science; metal oxide; Metallic films; Microstructure; nitinol; optical density; Oxide films; Polarization; priority journal; simulation; sodium chloride; Stainless steel; structure analysis; Surgery; Tantalum; Tantalum compounds; tantalum oxide; unclassified drug

Mathematical model for educational simulation of the oxygen delivery to the fetus - Sá Couto, P.M.; van Meurs, W.L.; Bernardes, J.F.; Marques De Sá, J.P.; Goodwin, J.A. (Control Engineering PracticeControl Eng. Pract., 2002)
Critical situations in obstetrics and anesthesia of the pregnant woman are rare and associated with a high risk to the woman and fetus involved. Therefore, simulation is a valuable tool in teaching the diagnostic and therapeutic skills in this context. We derive a mathematical model for the oxygen supply to the fetus that was specifically designed for educational simulations. The model reflects the hemodynamics and the oxygen transport. Parameter values for human patients are derived from the literature data. We validate the response of the model, with parameters reflecting the fetal lamb, to various reductions of the uterine and umbilical blood flow. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: COEPEdoi: 10.1016/S0967-0661(01)00133-2Language of Original Document: EnglishCorrespondence Address: Marques de Sá, J.P.; Instituto de Engenharia Biomedica, Faculdade de Engenharia, Universidade do Porto, Rua Roberto Frias, Porto 4200-465, Portugal; email: jmsa@fe.up.ptReferences: Beneken, J.E.W., Rideout, V.C., The use of multiple models in cardiovascular system studies: Transport and perturbation methods (1968) IEEE Transactions on Bio-Medical Engineering, 15 (4), pp. 281-289;Cunningham, G., (1997) Williams Obstretrics, , (20th ed.). London: Prentice-Hall; Delivoria-Papadopoulos, M., McGowan, J.E., Oxygen transport and delivery (1998) Fetal and Neonatal Physiology, pp. 1105-1117. , R. A. Polin and W. W. Fox (Eds.), (2nd ed.) London: W.B. Saunders Company; Euliano, T.Y., Caton, D., van Meurs, W.L., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) Journal Clinical Monitoring, 13 (5), pp. 293-297; Fukui, Y., Smith, N.T., Interactions among ventilation, the circulation, and the uptake and distribution of halothane-use of a hybrid computer multiple model: I the basic model (1981) Anesthesiology, 54, pp. 107-118; Fukui, Y., Smith, N.T., Interactions among ventilation, the circulation, and the uptake and distribution of halothane-use of a hybrid computer multiple model: II spontaneous vs. controlled ventilation, and the effects of CO 2 (1981) Anesthesiology, 54, pp. 119-124; Gaba, D.M., De Anda, A., A comprehensive anesthesia simulation environment: Recreating the operating room for research and training (1988) Anesthesiology, 69, pp. 387-394; Good, M.L., Gravenstein, J.S., Anesthesia simulators and training devices (1989) International Anesthesiololy Clinics, 27 (3), pp. 161-168; Guyton, A.C., (1991) Medical Physiolology, , (8th ed.). London: W.B. Saunders Company; Henson, L., Lee, A., (1998) Simulators in Anesthesiology Education, , New York: Plenum; Huikeshoven, F.J., Hope, I.D., Power, G.G., Gilbert, R.D., Longo, L.D., Mathematical model of fetal circulation and oxygen delivery (1985) American Journal of Physiology, 249, pp. R192-R202; Itskovitz, J., LaGamma, E., Rudolph, A.M., The effect of reducing umbilical blood flow on fetal oxygenation (1983) American Journal of Obstetric and Gynecology, 145 (7), pp. 813-818; Polin, R.A., Fox, W.W., (1998) Fetal and Neonatal Physiology, , (2nd ed.). London: W.B. Saunders Company; Schwid, H.A., Flight simulator for general anesthesia training (1987) Computers and Biomedical Research, 20, pp. 64-75; Schwid, H.A., O'Donnell, D., The anesthesia simulator- recorder: A device to train and evaluate anesthesiologists' responses to critical incidents (1990) Anesthesiology, 72, pp. 191-197; Severinghaus, J.W., Simple, accurate equations for human blood O 2 dissociation computations (1979) Journal of Applied Physiology, 46 (3), pp. 599-602; Skillman, C.A., Plemessinger, M.A., Woods, J.R., Clark, K.E., The effect of graded reductions in uteroplacental blood flow on fetal lamb (1985) American Journal of Physiology, 249 (18), pp. H1098-H1105; Sukumar, N., Morin III, F.C., Response of the fetal circulation to stress (1998) Fetal and Neonatal Physiology, pp. 1014-1023. , (2nd ed.) London: WB Saunders Company; van Meurs, W.L., Good, M., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) Journal of Clinical Monitoring, 13 (5), pp. 317-324; Zwart, A., Smith, N.T., Beneken, J.E.W., Multiple model approach to uptake and distribution of halothane: The use of an analog computer (1972) Computers and Biomedical Research, 5, pp. 228-238
Keywords: Anesthesiology; Blood; Computer simulation; control; Diagnosis; education; Fetal monitoring; fetus; hemodynamics; mathematical model; Mathematical models; medical application; Obstetrics; oxygen; Oxygen supply; simulator; Therapeutic skills

A novel urethane containing copolymer as a surface modification additive for blood contact materials - Ji, J.; Barbosa, M.A.; Feng, L.; Shen, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
Surface modification to develop a biomolecules-presenting surface is of interest, both from a scientific and an industrial point of view. In this research, a penta-block-coupling polymer of warfarin-PEO-MDI-PEO-warfarin was specially designed as the surface modifying additive (SMA). The warfarin-modified polyurethane surfaces were then prepared by dip-coating method. Attenuated total reflection fourier transform infra-red (ATR-FTIR) spectra revealed that the urethane segments in the SMA could penetrate into the hard block of segmented polyurethane (SPU) via intermolecular hydrogen bonds. The X-ray photoelectron spectroscopy (XPS) results indicated that the intermolecular hydrogen bonds were strong enough to form stable warfarin-PEO composite surfaces in an aqueous environment. Fibrinogen and albumin adsorption onto unmodified and SMA-modified SPU was investigated by the 125l-labeled method. The surface for attracting and reversibly binding albumin, which was proved to suppress the platelet adhesion and prolong the clotting time, has been developed by the simple coating of the novel SMA in SPU. © 2002 Kluwer Academic Publishers.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1015789726455Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, HangZhou 310027, China; email: jianji@mail.hz.zj.cnReferences: Elbert, D., Hubbell, J., (1996) Annu. Rev. Mater., p. 365;Munro, M., Quattrone, A., Ellsworth, S., Kulkarni, P., Eberhart, R., (1981) Trans. Am. Soc. Artif. Intern. Organs., p. 499; Park, K., Okano, T., Nojiri, C., Kim, S., (1988) J. Biomed. Mater. Res., p. 977; Han, D., Jeong, S., Kim, Y., Min, B., Cho, H., (1991) J. Biomed. Mater. Res., p. 561; Ji, J., Feng, L.X., Barbosa, M.A., (2001) Biomaterials, 22, p. 3015; Ji, J., Feng, L.X., Qiu, Y.X., Yu, X.J., Barbosa, M.A., (2000) J. Colloid Interfac. Sci., 15, p. 224; (2000) J. Colloid Interfac. Sci., 15, pp. 255-260; Ji, J., Feng, L.X., Qiu, Y., Yu, X., (2000) Polymer, p. 3713; Ishihara, K., Hanyuda, H., Nakabayashi, N., (1995) Biomaterials, p. 873; Amiji, M., Park, K., (1993) J. Biomater. Sci. Polym. Ed., p. 217; Lamba, N., Woodhouse, K., Cooper, S.L., (1998) Polyurethanes in Biomedical Applications, p. 43. , CRC Press, New York; Nelson, K.D., Eisenbaumer, R., Pomerantz, M., Eberhart, R.C., (1996) ASAIO Journal, p. 884; Wang, D.A., Ji, J., Feng, L.X., (2000) Macromol. Chem. Phys., p. 1574; Wang, D.A., Ji, J., Feng, L.X., (2000) Macromolecules, p. 8472; Brash, J.L., Davidson, V.J., (1976) Thromb. Res., p. 249; Qiu, Y.X., Yu, X.J., Feng, L.X., (1992) Markromol. Chem., p. 1377; Okkema, A.Z., Grasel, T.G., Zdrahala, R.J., Solomon, D.D., Cooper, S.L., (1989) J. Biomater. Sci. Polym. Ed., p. 43; Takahara, A., Jujo, A.N., Kajiyama, N.T., (1989) J. Biomater. Sci. Polym. Ed., p. 17
Keywords: Adhesion; Adsorption; Albumin; article; Attenuation; biomaterial; Block copolymers; Blood; blood clotting time; Chemical modification; Coatings; copolymer; fibrinogen; Fourier transform infrared spectroscopy; human; human cell; hydrogen bond; Hydrogen bonds; infrared spectroscopy; iodine 125; material coating; Polyurethanes; priority journal; Surface modifying additives (SMA); surface property; Surface treatment; synthesis; thrombocyte adhesion; urethan; warfarin; X ray photoelectron spectroscopy

Porous glass reinforced hydroxyapatite materials produced with different organic additives - Prado da Silva, M.H.; Lemos, A.F.; Gibson, I.R.; Ferreira, J.M.F.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2002)
In the present study three different organic additives were used to produce porous structures of a CaO-P 2O 5 glass reinforced hydroxyapatite potato starch, almond crust and wax spheres. The produced samples were analysed by scanning electron microscopy, X-ray diffraction with Rietveld refinement, differential thermal analysis and mercury porosimetry. The techniques used in this study enabled the production of glass reinforced hydroxyapatite samples with various pore diameters. Two different techniques were used to produce porous glass reinforced hydroxyapatite samples: a dry method using wax spheres as pore formers and a wet method in alcoholic suspension, where almond crust and potato starch were used as pore formers. The final microstructure consists of hydroxyapatite, α-tricalcium phosphate and β-tricalcium phosphate. X-ray diffraction and scanning electron microscopy analysis revealed different percentages of phases when comparing dense and porous glass reinforced hydroxyapatite specimens. These hard materials are intended to be used as bone defect fillers. © 2002 Elsevier Science B.V. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: JNCSBdoi: 10.1016/S0022-3093(02)01036-0Language of Original Document: EnglishCorrespondence Address: Prado da Silva, M.H.; DEM, Universidade Federal do Ceara, PO Box 12144, 60455-760 Fortaleza, CE, Brazil; email: mpsilva@ibmc.up.ptReferences: Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (2000) Biomaterials, 21, p. 813;Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 47, p. 603; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 45, p. 376; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) Surf. Coat. Tech., 102, p. 191; Zhang, Y., Santos, J.D., (2000) J. Non-Cryst. Solids, 272, p. 14; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mater. Sci: Mat. Med., 6, p. 348; Santos, J.D., Jha, L.J., Monteiro, F.J., (1996) J. Mater. Sci: Mater. Med., 7, p. 181; Lemos, A.F., Ferreira, J.M.F., (2000) Mater. Sci. Eng, 11, p. 35; Lyckfeldt, O., Ferreira, J.M.F., (1998) J. Eur. Ceram. Soc., 18, p. 131; Saggio-Woyansky, J., Scott, C.E., Minnear, W.P., (1992) Am. Ceram. Soc. Bull., 71, p. 1674; De Groot, K., Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., (1990) Hand. Bioact. Cer., 2, p. 3. , CRC, Boca Raton, FL; Knowles, J.C., Santos, J.D., Hastings, G.W., patent number WO0068164, 2000Larson, A.C., Von Dreele, R.B., Lujan M., Jr., GSAS, Neutron Scattering Centre, Los Alamos National Laboratory, CA, 1990Kay, M.I., Young, R.A., Posner, A.S., (1964) Nature, 204, p. 1050; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244
Keywords: Additives; Differential thermal analysis; Fillers; glass; hydroxyapatite; Microstructure; Porosimeters; Porous glasses; Porous materials; Scanning electron microscopy; Suspensions (fluids); X ray diffraction analysis

Preparation of albumin preferential surfaces on poly(vinyl chloride) membranes via surface self-segregation - Ji, A.; Feng, L.; Shen, J.; Barbosa, M.A. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2002)
Poly(vinyl chlorides)-graft-[w-stearyl-poly(ethylene oxide)] (PVC-g-SPEO), which has a poly(vinyl chloride) (PVC) backbone, poly(ethylene oxide) (PEO) side chain, and stearyl end groups, has been synthesized. Self-organizing blends of the amphiphilic comb polymer in poly-(vinyl chlorides) have been examined as a means to create albumin preferential surfaces on polymer films. X-ray photoelectron spectroscopy (XPS) analysis indicates substantial surface segregation of the PVC-g-SPEO. A surface concentration of 59.9 EO wt % is achieved by the solution casting and heat treatment of a film with a bulk concentration of only 3.78 EO wt %. In the aqueous environment, the surface rearrangement of PVC-g-SPEO/PVC blend film is limited and presents a high interfacial energy and high depolar component of interfacial energy due to the "tail-like" SPEO side chain. Protein adsorption tests confirm that PVC-g-SPEO/PVC blend films absorb high levels of albumin and dramatically resist fibrinogen adsorption. Surfaces to attract and reversibly bind albumin, which might diminish the occurrence of thrombosis, inflammation, and infection, are developed by self-organizing blends of the amphiphilic comb polymer in poly(vinyl chlorides). © 2002 Wiley Periodicals, Inc.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/jbm.10187Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, HangZhou, 310027, China; email: jianji@mail.hz.zj.cnChemicals/CAS: Membranes, Artificial; Polyethylene Glycols; Polyvinyl Chloride, 9002-86-2; Serum Albumin; Stearates; stearyl poly(ethylene oxide)References: Blass, C.R., Jones, C., Courtney, J.M., Biomaterials for blood tubing: The application of plasticised poly(vinyl chloride) (1992) Int J Artif Organs, 15 (4), pp. 200-203;Brash, J.L., (1983) Biocompatible polymer, metals and composites, p. 35. , Szycher M, editor. London, UK: Technomic Pub. Co; Keogh, J.R., Velander, F.F., Eaton, W., Albumin-binding surfaces for implantable devices (1992) J Biomed Mater Res, 26 (4), pp. 441-456; Amiji, M., Park, K., Surface modification of polymeric biomaterials with poly(ethylene oxide), albumin, and heparin for reduced thrombogenicity (1993) J Biomater Sci Polym Ed, 4 (3), pp. 217-234; Ji, J., Feng, L., Barbosa, M.A., Stearyl poly(ethylene oxide) grafted surfaces as albumin preferential materials (2001) Biomaterials, 22, p. 3015; De Queiroz, A.A., Barrak, E.R., Gil, H.A., Higa, O.Z., Surface studies of albumin immobilized onto PE and PVC films (1997) J Biomater Sci Polym Ed, 8 (9), pp. 667-681; McFarland, C.D., Jenkins, M., Griesser, H.J., Chatelier, R.C., Steele, J.G., Underwood, P.A., Albumin-binding surfaces: Synthesis and characterization (1998) J Biomater Sci Polym Ed, 9 (11), pp. 1207-1225; Wang, D.A., Ji, J., Sun, Y.H., Yu, G.H., Feng, L.X., Blends of stearyl poly(ethylene oxide) coupling-polymer in chitosan as coating materials for polyurethane intravascular catheters (2001) J Biomed Mater Res, 58 (4), pp. 372-383; Wang, D.A., Ji, J., Gao, C.Y., Yu, G.H., Feng, L.X., Surface coating of stearyl poly(ethylene oxide) coupling-polymer on polyurethane guiding catheters with poly(ether urethane) film-building additive for biomedical applications (2001) Biomaterials, 22 (12), pp. 1549-1562; Ji, J., Feng, L., Qiu, Y., Yu, X., Barbosa, M.A., Self-assembly and surface structure of an amphiphilic graft copolymer, polystyrene-graft-omega-stearyl-poly(ethylene oxide) (2000) J Colloid Interface Sci, 224 (2), pp. 255-260; Jian, J., Feng, L., Qiu, Y., Yu, X., Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin Part 2 (2000) The effect of molecular mobility on protein adsorption Polymer, 41 (10), pp. 3713-3718; Wu, S., (1982) Polymer Interface and adhesion, , New York: Marcel Dekker; Garbassi, F., Morra, M., Occhliello, E., (1994) Polymer surface: From physics to technology, , New York: John Wiley & Sons; Walton, D.G., Mayes, A.M., Entropically-driven segregation in blend of branch and linear polymers (1996) Phys Rev E, 54 (3), pp. 2811-2815; Mayes, A.M., Irvine, D.J., Griffith, L.G., Tailoring polymer surfaces for control cell behavior (1998) Biomaterials regulating cell function and tissue development, pp. 73-86. , Thomson RC, Mooney DJ, Healy KE, Ikada T, Mikos AG, editors. Warrendale: Materials Research Society; Eberhart, R.C., Munro, M.S., Williams, G.B., Kulkarni, P.V., Shannon W.A., Jr., Brink, B.E., Fry, W.J., Albumin adsorption and retention on C18-alkyl-derivatized polyurethane vascular grafts (1987) Artif Organs, 11 (5), pp. 375-382; Grasel, T.G., Pierce, J.A., Cooper, S.L., Effects of alkyl grafting on surface properties and blood compatibility of polyurethane block copolymers (1987) J Biomed Mater Res, 21 (7), pp. 815-842; Gombotz, W.R., Guanghui, W., Horbett, T.A., Hoffman, A.S., Protein adsorption to poly(ethylene oxide) surfaces (1991) J Biomed Mater Res, 25 (12), pp. 1547-1562; Neumann, A.W., Goog, R.J., Surface and colloid science, experimental methods (1979), 11, p. 31. , New York: Plenum PressAndrade, J.D., Ma, S.M., Contact angle at the S-W interface (1979) J Colloid Interface Sci, 72, pp. 488-494; Brash, J.L., Davidson, V.J., Adsorption of glass and polyethylene from solutions of fibrinogen and albumin (1976) Thromb Res, 9 (3), pp. 249-259; Ranter, B.D., (1985) Surface and interfacial aspects of biomedical polymers, p. 374. , Andrade JD, editor. New York: Plenum Press; Van Oss, C.J., (1994) Interfacial forces in aqueous media, pp. 170-177. , Van Oss CJ, editor. New York: Marcel Dekker; Wu, D., Jian, K., (1995) Sci China (B), 25 (11), p. 1121; Wu, D., (1995) Jian K Sci China (B), 26 (5), p. 409; Jeon, S.I., Lee, J.H., Andrade, J.D., De Gennes, P.G., Protein-surface interactions in the presence of polyethylene oxide (1991) J Coll Interface Sci, 142 (1), pp. 149-158; Hester, J.F., Banerjee, P., Mayes, A.M., Preparation of protein-resistant surfaces on poly(vinylidene fluoride) membranes via surface segregation (1999) Macromolecules, 32 (5), pp. 1643-1650; Keogh, R.J., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 124 (4), pp. 537-545
Keywords: Adsorption; Albumin; Amphiphilic copolymer; amphophile; aqueous solution; article; artificial membrane; Biocompatible Materials; cell separation; cell surface; chemical binding; combinatorial chemistry; concentration response; conference paper; dimerization; energy resource; film; human; Humans; infection; Inflammation; Inflammations; macrogol; macrogol derivative; membrane structure; Membranes, Artificial; metabolism; Plastic films; Polyethylene Glycols; polymer; Polymeric membranes; Polyvinyl Chloride; Polyvinyl chlorides; polyvinylchloride; protein binding; Serum Albumin; Stearates; stearic acid derivative; stearyl poly(ethylene oxide); Surface modification; Surface Properties; surface property; Surface segregation; Synthesis (chemical); thrombosis; X ray analysis; X ray photoelectron spectroscopy

Production of porous biomaterials based on glass-reinforced hydroxyapatite composites - Prado da Silva, M.H.; Lemos, A.F.; Ferreira, J.M.F.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2002)
In this study, porous GR-HA composites were produced using a calcium-phosphate glass with the composition, in mol%, 75P 2O 5-15CaO-10CaF 2. The composites were obtained by wet mixing 4.0% (w/w) of the glasses with hydroxyapatite (HA) powder (batch P120) (Plasma Biotal; Tideswell, U.K.), pressing and sintering. Two different organic additives were used as pore formers: potato starch and almond crust. This processing route was effective in producing a homogeneous microstructure of equiaxed grains. The bulk density of the samples decreased with the volume fraction increase in the content of pore formers. Scanning electron microscopy and mercury porosimetry analyses showed to be complementary techniques in characterising the pore size and distribution.
Conference code: 60281Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Prado da Silva, M.H.; Instituto de Engenharia Biomedica, Laboratório de Biomaterials, Rua do Campo Alegre 823, PT-4150-180 Porto, PortugalReferences: Lemos, A.F., Ferreira, J.M.F., (2000) Materials Science and Engineering, 11, pp. 35-40;Saggio-Woyansky, J., Scott, C.E., Minnear, W.P., (1992) Amer. Cer. Society Bulletin, 71 (11), pp. 1674-1682; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inouue, H., (2001) J. Biom. Mater. Res., 54, pp. 463-469; Knowles, J.C., Santos, J.D., Hastings, G.W., (2000) Sintered Hydroxyapatite Composition and Method for the Preparation thereof, , Patent number WO0068164
Keywords: Biomaterials; Composite materials; glass; Glass-reinforced hydroxyapatite composites; GR-HA Composites; hydroxyapatite; Macroporous Bioceramics; Mercury (metal); Microstructure; Organic Additives; Pore size; Porous materials; Powders; Pressing (forming); Scanning electron microscopy; Sintering; Starch

Real-time implementation of an optical flow algorithm - Correia, M.V.; Campilho, A.C. (Proceedings - International Conference on Pattern RecognitionProc. Int. Conf. Pattern Recognit., 2002)
This paper presents the implementation of an optical flow algorithm on a pipeline image processor. The overall optical flow computation method is presented and evaluated on a common set of image sequences. Results are compared to other implementations according to two different error measures. Due to its deterministic architecture, this implementation achieves very low computation delays that allow it to operate at standard video frame-rate and resolutions. It compares favorably to recent implementations in parallel hardware. © 2002 IEEE.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: PICRELanguage of Original Document: EnglishCorrespondence Address: Correia, M.V.; Instituto de Engenharia Biomédica, Faculdade de Engenharia, Dept. Eng. Electrotécnica e de Computadores, R. Dr. Roberto Frias, 4200-465 Porto, Portugal; email: mcorreia@fe.up.ptReferences: Barron, J.L., Fleet, D.J., Beauchemin, S.S., Performance of optical flow techniques (1994) International Journal of Computer Vision, 12 (1), pp. 43-77;Correia, M.V., Campilho, A.C., Santos, J.A., Nunes, L.B., Optical flow techniques applied to the calibration of visual perception experiments (1996) Proceedings of 13th International Conference on Pattern Recognition, ICPR '96, pp. 498-502. , Vienna, Austria, August; Fleet, D.J., Langley, K., Recursive filters for optical flow (1995) IEEE Transactions on Pattern Analysis and Machine Intelligence, 17 (1), pp. 61-67. , January; Fleury, M., Clark, A.F., Downton, A.C., Evaluating optical-flow algorithms on a parallel machine (2001) Image and Vision Computing, 19, pp. 131-143; Lin, T., Barron, J.L., Image reconstruction error for optical flow (1994) Proceedings of Vision Interface'94, pp. 73-80. , Banff National Park, Canada, May; Liu, H., Hong, T.-H., Herman, M., Camus, T., Accuracy vs efficiency trade-offs in optical flow algorithms (1998) Computer Vision and Image Understanding, 72 (3), pp. 271-286. , December; Lucas, B.D., (1984) Generalized Image Matching by the Method of Differences, , PhD thesis, Carnegie Mellon University; Olson, T.J., Taylor, J.R., Lockwood, R.J., Programming a pipelined image processor (1996) Computer Vision and Image Understanding, 64 (3), pp. 351-367. , November; Santos, J., Noriega, P., Correia, M., Campilho, A., Albuquerque, P., (2000) Object Motion Segmentation and Optical Flow Contrast, , Relatórios de investigação C.E.E.P., Universidade do Minho, Braga; Simoncelli, E.P., (1993) Distributed Representation and Analysis of Visual Motion, , PhD thesis, Massachusetts Institute of Technology, January
Keywords: Algorithms; Computational methods; Image analysis; Image processors; Image sequences; Optical flow algorithm; Optical flows; Real time systems; Video frame-rate; Video signal processing

Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells - Amaral, M.; Costa, M.A.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2002)
The in vitro osteocompatibility of a novel Si 3N 4-bioglass composite (70-30% weight proportion) with improved mechanical properties (fracture toughness=4.4MPam 1/2; bending strength=383±47MPa) is reported. Immersion of the composite samples in culture medium (30min to 7 days) resulted in rapid protein adsorption to the surface and, also, dissolution of the intergranular phase of bioglass (time-dependent process) with the formation of different size cavities. "As-received" and pre-treated material samples presented a similar behaviour concerning the proliferation of MG63 osteoblast-like cells, evaluated during a 5-day culture period. Seeded materials showed a higher cell growth rate as compared to cultures performed on the standard plastic culture plates. To assess the osteogenic potential of the composite, "as-received" material samples were seeded with human bone marrow cells and cultured for 35 days in experimental conditions that favour the development of the osteoblastic phenotype. The cell adhesion process was similar to that observed in control cultures. Cells successfully adapted to the irregularities of the surface and were able to grow towards inside the cavities; in addition, osteogenic differentiation occurred with the formation of abundant cell-mediated mineralised deposits. Results suggest that this Si 3N 4-bioglass composite seems to be a promising candidate for high-stress medical applications. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00249-1PubMed ID: 12361631Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200-393 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Silicon Compounds; silicon nitride, 12033-89-5References: Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si 3N 4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862;Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride - Bioglass ® 45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblastic phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 43, pp. 213-221; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Stein, G.S., Lian, J.B., Stein, J.L., Van Wijnem, A.J., Frenkel, B., Montecino, M., Mechanisms regulating osteoblast proliferation and differentiation (1996) Principles of bone biology, pp. 69-86. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci: Mater Med, 8, pp. 61-65; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: Effect of ascorbic acid β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Costa, M.A., Fernandes, M.H., Long-term effects of parathyroid hormone, 1,25-dihydroxyvitamin D3 and dexamethasone on the cell growth and functional activity of human osteogenic alveolar bone cell cultures (2000) Pharmacol Res, 42, pp. 345-353; Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Aubin, J.E., Liu, F., The osteoblastic lineage (1996) Principles of bone biology, pp. 51-67. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro bioactivity evatuation (1999) J Biomed Mater Res, 45, pp. 376-383; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strenght bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Daculsi, G., Legeros, R.Z., Heughebaert, M., Barbieux, I., Formation of carbonato-apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46 (1), pp. 20-27; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J Biomed Mater Res, 27, pp. 999-1006; Bagambisa, F.B., Joos, U., Schilli, W., Mechanisms and structure of the bond between bone and hydroxyapatite ceramics (1993) J Biomed Mater Res, 27, pp. 1047-1055; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblast to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface (1995) J Biomed Mater Res, 29 (1), pp. 89-99; Hulshott, J.E.G., Van Kijk, K., De Ruijter, J.E., Rietveld, F.J.R., Ginsel, L.A., Jansen, J.A., Interfacial phenomena: An in vitro study of the effect of calcium phosphate (Ca-P) ceramic on bone formation (1998) J Biomed Mater Res, 40, pp. 464-474; De Santis, D., Guerriero, C., Nocini, P.F., Vangersbock, A., Richard, G., Gotte, P., Armato, U., Adult human bone cells from jaw bones cultured on plasma-sprayed or polished surfaces of titanium or hydroxyapatite discs (1996) J Mater Sci Mater Med, 7, pp. 21-28; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., In vitro growth of human adult bone-derived cells on hydroxyapatite plasma-sprayed coatings (1997) J Biomed Mater Res, 34, pp. 247-259; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblastic-like human bone marrow cells on a glass reinforced hydroxyapatite plasma-speayed coating (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and double-layer HA/CaO-P 2O 5 glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 7, pp. 628-638; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite composites on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gwynn, I.A.P., Cell biology at interfaces (1994) J Mater Sci Mater Med, 5, pp. 357-360; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; KirkPatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., The cell and molecular biological approach to biomaterial research: A perspective (1997) J Mater Sci Mater Med, 8, pp. 131-141; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amedee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci Mater Med, 7, pp. 46-51; Dee, K.C., Rueger, D.C., Andersen, T.T., Bizios, R., Conditions which promote mineralization at the bone-implant interface: A model for in vitro study (1996) Biomaterials, 17, pp. 209-215; Anseme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Diniz, M.G., Soares, G.A., Coelho, M.J., Fernandes, M.H., Surface topography modulates the osteogenesis in human bone marrow cell cultures grown on titanium samples prepared by a combination of mechanical and acid treatments (2002) J Mater Sci: Mater Med, 13, pp. 421-432; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29
Keywords: 3N; 4-bioglass composite; Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; Bioglass; Biomaterials; bone marrow cell; Bone Marrow Cells; Calcium; cell adhesion; Cell Culture Techniques; cell differentiation; Cell Division; cell growth; cell proliferation; composite material; controlled study; culture medium; Dissolution; glass; Growth kinetics; human; Human bone marrow cells; human cell; Humans; immersion; in vitro study; Mechanical properties; MG63 osteoblast-like cells; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; Osteocompatibility; Osteogenic differentiation; phenotype; phosphorus; priority journal; Proteins; rigidity; Si; Silicon compounds; silicon derivative; surface property; tensile strength; Time Factors

Silicon and iron levels in tissues of animals treated with a "ferrimagnetic ceramic" with oncotherapeutic potential (anti-tumor) value - Almeida, T.; Soares, M.E.; Cavalheiro, J.; Bastos, M.D.L. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 2002)
The stability in a biological environment of an injectable cement with oncotherapeutic potential - consisting of a glass powder of SiO 2 (35.6%), CaO (42.4%), P 2O 5 (17%), Na 2O (5%) and 30% of its weight of Fe 3O 4 dissolved in (NH 4) 2HPO 4 plus NH 4H 2PO 4 - was evaluated referring to the release of silicon and iron. The experimental model was the rat, and organs (liver, kidney, spleen, lung, heart, and brain) of the implanted and control animals were collected for quantification of these elements by electrothermal atomization atomic absorption spectrometry methods. In most of the analysed organs no significant difference in the contents of silicon and iron between the implanted and the control animals was found.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JTEBFdoi: 10.1016/S0946-672X(02)80054-2PubMed ID: 12530589Language of Original Document: EnglishCorrespondence Address: Bastos, M.D.L.; Toxicology Department, Faculty of Pharmacy, University of Porto, Rua Aníbal Cunha 164, 4050 Porto, PortugalChemicals/CAS: calcium oxide, 1305-78-8; iron, 14093-02-8, 53858-86-9, 7439-89-6; phosphorus pentoxide, 1314-56-3; silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; silicon, 7440-21-3; Biocompatible Materials; Ceramics; Iron, 7439-89-6; Silicon, 7440-21-3; Tissue ExtractsReferences: Rofstad, E.K., Brustad, T., Primary and secondary cell death in human melanoma xenografts following hyperthermic treatment (1986) Cancer Res., 46, pp. 355-361;Nishimura, Y., Shibamoto, Y., Jo, S., Akuta, K., Hiraoka, M., Takahashi, M., Abe, M., Relationship between heat-induced vascular damage and thermosensitivity in four mouse tumors (1988) Cancer Res., 48, pp. 7226-7230; Brown, S.L., Hunt, J.W., Hill, R.P., Differential thermal sensitivity of tumour and normal tissue microvascular response during hyperthermia (1992) Int. J. Hyperthermia, 8, pp. 501-514; Dudar, T.E., Jain, R.K., Differential response of normal and tumor microcirculation to hyperthermia (1984) Cancer Res., 44, pp. 605-612; Hill, S.A., Smith, K.A., Denekamp, J., Reduced thermal sensitivity of the vasculature in a slowly growing tumour (1989) Int. J. Hyperthermia, 5, pp. 359-370; Bicher, H.I., Hetzel, F.W., Sandhu, T.S., Frinak, S., Vaupel, P., O'Hara, M.D., O'Brien, T., Effects of Hyperthermia on normal and tumor microenvironment (1980) Radiology, 137, pp. 523-530; Song, C.W., Kang, M.S., Rhee, J.G., Levitt, S.H., The effect of hyperthermia on vascular function, pH, and cell survival (1980) Radiology, 137, pp. 795-803; Emami, B., Song, C.W., Physiological mechanisms in hyperthermia: A review (1984) Int. J. Radiation Oncology Biol. Phys., 10, pp. 289-295; Cavalheiro, J., Vasconcelos, M., Afonso, A., Branco, R., Ferrimagnetic and biocompatible cement for tumours thermotherapy (1996) Bioceramics, 9, pp. 243-246; Coury, A.J., Levy, R.J., McMillin, C.R., Pathak, Y., Ratner, B.D., Schoen, F.J., Williams, D.F., Williams, R.L., Degradation of materials in the biological environment (1996) Biomaterials Science, pp. 243-260. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Williams, D.F., Williams, R.L., Degradative effects of the biological environment on metals and ceramics (1996) Biomaterials Science, pp. 260-267. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Van Dyck, K., Robberecht, H., Van Cauwenbergh, R., Deelstra, H., Arnaud, J., Willemyns, L., Benijts, F., Uytterhoeven, M., Spectrometric determination of silicon in food and biological samples: An interlaboratory trial (2000) J. Anal. At. Spectrom., 15, pp. 735-741; Adler, A.J., Etzion, Z., Berlyne, G.M., Uptake, distribution, and excretion of 31silicon in normal rats (1986) Am. J. Physiol., 251, pp. E670-E673; Beattie, J.H., Avenell, A., Trace element nutrition and bone metabolism (1992) Nutrition Res. Rev., 5, pp. 167-188; Robinson, C.H., Lawler, M.R., Mineral elements (1982) Normal and Therapeutic Nutrition, 16 th Edition, pp. 131-160. , Robinson CH, Lawler MR (Eds). Macmillan Publishing Co., Inc., New York, Collier Macmillan Publishers, London; Sorond, F.A., Ratan, R.R., Ironing-out mechanisms of neuronal injury under hypoxic-ischemic conditions and potential role of iron chelators as neuroprotective agents (2000) Antioxid. Redox Signal, 2, pp. 421-436; Bonkovsky, H.L., Lambrecht, R.W., Iron-induced liver injury (2000) Clin. Liver Dis., 4, pp. 409-429; Bartfay, W.J., Bartfay, E., Iron-overload cardiomyopathy: Evidence for a free radical-mediated mechanism of injury and dysfunction in a murine model (2000) Biol. Res. Nurs., 2, pp. 49-59; Kang, J.L., Pack, I.S., Lee, H.S., Castranova, V., Enhancement of nuclear factor-KB activation and protein tyrosine phosphorylation by a tyrosine phosphatase inhibitor, pervanadate, involves reactive oxygen species in silica-stimulated macrophages (2000) Toxicology, 151, pp. 81-89
Keywords: animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; calcium oxide; cancer therapy; cement; ceramics; controlled study; experimental model; Ferrimagnetic ceramic; heat; Humans; implant; Iron; Magnetics; materials testing; Neoplasms; nonhuman; Oncotherapy; phosphorus pentoxide; powder; priority journal; Prostheses and Implants; rat; Rats; Reproducibility of Results; Silicon; silicon dioxide; tissue distribution; Tissue Extracts

Soluble silk-like organic matrix in the nacreous layer of the bivalve Pinctada maxima: A new insight in the biomineralization field - Pereira-Mouriès, L.; Almeida, M.-J.; Ribeiro, C.; Peduzzi, J.; Barthélemy, M.; Milet, C.; Lopez, E. (European Journal of BiochemistryEur. J. Biochem., 2002)
Nacre organic matrix has been conventionally classified as both 'water-soluble' and 'water-insoluble', based on its solubility in aqueous solutions after decalcification with acid or EDTA. Some characteristics (aspartic acid-rich, silk-fibroin-like content) were specifically attributed to either one or the other. The comparative study on the technique of extraction (extraction with water alone vs. demineralization with EDTA) presented here, seems to reveal that this generally accepted classification may need to be reconsidered. Actually, the nondecalcified soluble organic matrix, extracted in ultra-pure water, displays many of the characteristics of what until now has been called 'insoluble matrix'. We present the results obtained on this extract and on a conventional EDTA-soluble matrix, with various characterization methods: fractionation by size-exclusion and anion-exchange HPLC, amino acid analysis, glycosaminoglycan and calcium quantification, SDS/PAGE and FTIR spectroscopy. We propose that the model for the interlamellar matrix sheets of nacre given by Nakahara [In: Biomineralization and Biological Metal Accumulation, Westbroek, P. & deJong, E.W., eds, (1983) pp. 225-230. Reidel, Dordrecht, Holland] and Weiner and Traub [Phil. Trans. R. Soc. Lond. B (1984) 304, 425-434] may no longer be valid. The most recent model, proposed by Levi-Kalisman et al. [J. Struct. Biol. (2001) 135, 8-17], seemed to be more in accordance with our findings.
Cited By (since 1996): 58Export Date: 21 November 2012Source: ScopusCODEN: EJBCAdoi: 10.1046/j.1432-1033.2002.03203.xPubMed ID: 12383258Language of Original Document: EnglishCorrespondence Address: Lopez, E.; Lab. de Physiologie Gen. et Comparee, UMR CNRS 8572, Museum National d'Histoire Naturelle, 7 rue Cuvier, 75231 Paris Cedex 05, France; email: lopez@mnhn.frChemicals/CAS: Amino Acids; Calcium, 7440-70-2; Edetic Acid, 60-00-4; Extracellular Matrix Proteins; Glycosaminoglycans; Insect Proteins; SilkReferences: Crenshaw, M.A., The soluble matrix from Mercenaria mercenaria shell (1972) Biomineralization, 6, pp. 6-11;Krampitz, G., Engels, J., Cazaux, C., Biochemical studies on water-soluble proteins and related components of gastropod shells (1976) The Mechanisms of Mineralization in the Invertebrates and Plants, pp. 175-190. , Watabe, N. & Wilbur, K.M., eds. The Barush B.W. Library in Marine Science no. 5, The University of South Carolina Press, Columbia; Weiner, S., Traub, W., Lowenstam, H.A., Organic matrix in calcified exoskeletons (1983) Biomineralization and Biological Metal Accumulation, pp. 205-224. , Westbroek, P. & deJong, E.W., eds. Reidel, Dordrecht, Holland; Keith, J., Stockwell, D., Ball, D., Remillard, K., Kaplan, D., Thannhauser, T., Sherwood, R., Comparative analysis of macromolecules in mollusc shells (1993) Comp. Biochem. Physiol., 105 B, pp. 487-496; Levi-Kalisman, Y., Falini, G., Addadi, L., Weiner, S., Structure of the nacreous organic matrix of a bivalve mollusk shell examined in the hydrated state using cryo-TEM (2001) J. Struct. Biol., 135, pp. 8-17; Weiner, S., Hood, L., Soluble protein of the organic matrix of mollusk shells: A potential template for shell formation (1975) Science, 190, pp. 987-989; Weiner, S., Traub, W., Macromolecules in mollusc shells and their functions in biomineralization (1984) Phil. Trans. R. Soc. Lond. B, 304, pp. 425-434; Belcher, A.M., Wu, X.H., Christensen, R.J., Hansma, P.K., Stucky, G.D., Morse, D.E., Control of crystal phase switching and orientation by soluble mollusc-shell proteins (1996) Nature, 381, pp. 56-58; Kamat, S., Su, X., Ballarini, R., Heuer, A.H., Structural basis for the fracture toughness of the shell of the conch Strombus gigas (2000) Nature, 405, pp. 1036-1040; Hare, P.E., Amino acids in the proteins from aragonite and calcite in the shells of Mytilus californianus (1963) Science, 139, pp. 216-217; Hare, P.E., Abelson, P.H., Amino acid composition of some calcified proteins (1965) Carnegie Inst. Washington Year Book, 64, p. 223; Watabe, N., Shell (1984) Biology of the Integument, 1, pp. 448-485. , Invertebrates (Bereiterhahn, J., Matolsty, A.G. & Richards, K.S., eds). Springer-Verlag, Berlin; Mann, S., Molecular recognition in biomineralization (1988) Nature, 332, pp. 119-124; Kono, M., Hayashi, N., Samata, T., Molecular mechanism of the nacreous layer formation in Pinctada maxima (2000) Biochem. Biophys. Res. Commun., 269, pp. 213-218; Lopez, E., Berland, S., Le Faou, A., Nacre, osteogenic and osteoinductive properties (1994) Bull. Inst. Océan Monaco, 14, pp. 49-57; Lopez, E., Vidal, B., Berland, S., Camprasse, C., Camprasse, G., Silve, C., Demonstration of the capacity of nacre to induce bone formation by human osteoblasts maintained in vitro (1992) Tissue Cell, 24, pp. 667-679; Atlan, G., Balmain, N., Berland, S., Vidal, B., Lopez, E., Reconstruction of human maxillary defects with nacre powder: Histological evidence for bone regeneration (1997) C. R. Acad. Sci. Paris, Life Sci., 320, pp. 253-258; Atlan, G., Delattre, O., Berland, S., Le Faou, A., Nabias, G., Cot, D., Lopez, E., Interface between bone and nacre implants in sheep (1999) Biomaterials, 20, pp. 1017-1022; Lamghari, M., Almeida, M.J., Berland, S., Huet, H., Laurent, A., Milet, C., Lopez, E., Stimulation of bone marrow cells and bone formation by nacre: In vivo and in vitro studies (1999) Bone, 25 S, pp. 91S-94S; Almeida, M.J., Milet, C., Peduzzi, J., Pereira, L., Haigle, J., Barthélemy, M., Lopez, E., The effect of water-soluble matrix fraction extracted from the nacre of Pinctada maxima on the alkaline phosphatase activity of cultured fibroblasts (2000) J. Exp. Zool. (Mol. Dev. Evol.), 288, pp. 327-334; Almeida, M.J., Pereira, L., Milet, C., Haigle, J., Barbosa, M., Lopez, E., Comparative effects of nacre water-soluble matrix and dexamethasone on the alkaline phosphatase activity of MRC-5 fibroblasts (2001) J. Biomed. Mater. Res., 57, pp. 306-312; Lamghari, M., Berland, S., Laurent, A., Huet, H., Lopez, E., Bone reactions to nacre injected percutaneously into the vertebrae of sheep (2001) Biomaterials, 22, pp. 555-562; Lopez, E., Giraud, M., Le Faou, A., Berland, S., Gutierrez, J., (1995), Procédé de préparation de substances actives à partir de la nacre, produits obtenus, utiles comme médicaments. Patent CNRS no. FR. 9515650, 28/12/1995, WO 97/24133-10/07/97Wheeler, A.P., Rusenko, K.W., George, J.W., Sikes, S., Evaluation of calcium binding by molluscan shell organic matrix and its relevance to biomineralization (1987) Comp. Biochem. Physiol., 87 B, pp. 953-960; Cohen-Solal, L., Lian, J.B., Kossiva, D., Glimcher, M.J., The identification of O-phosphothreonine with soluble non-collagenous phosphoproteins of bone matrix (1978) FEBS Lett., 89, pp. 107-110; Cohen, S.A., Strydom, D.J., Amino acid analyses utilizing phenylisothiocyanate derivatives (1988) Anal. Biochem., 174, pp. 1-16; Hewitt, B.R., Spectrophotometric determination of protein in alkaline solution (1958) Nature, 187, p. 246; Whiteman, P., The quantitative determination of glycosaminoglycans in urine with Alcian blue 8GX (1973) Biochem. J., 131, pp. 351-357; Whiteman, P., The quantitative measurement of Alcian blue-glycosaminoglycan complexes (1973) Biochem. J., 131, pp. 343-350; Gold, E.W., A simple spectrophotometric method for estimating glycosaminoglycan concentrations (1979) Anal. Biochem., 99, pp. 183-188; Laemmli, U.K., Cleavage of structural proteins during the assembly of the head of bacteriophage T4 (1970) Nature, 227, pp. 680-685; Morrissey, J.H., Silver stain for proteins in polyacrylamide gels: A modified procedure with enhanced uniform sensitivity (1981) Anal. Biochem., 117, pp. 307-310; Wheeler, A.P., Rusenko, K.W., Sikes, S., Organic matrix from carbonate biomineral as a regulator of mineralization (1988) Chemical Aspects of Regulation of Mineralization, , (Sikes, C.S. & Wheeler, A.P., eds). University of South Alabama Publication Services, Mobile, Alabama; Weiner, S., Aspartic acid-rich proteins: Major components of the soluble organic matrix of mollusk shells (1979) Calcif. Tissue Int., 29, pp. 163-167; Wheeler, A.P., Rusenko, K.W., Swift, D.M., Sikes, S., Regulation of in vitro and in vivo CaCO 3 crystallization by fractions of oyster shell organic matrix (1988) Mar. Biol., 98, pp. 71-80; Halloran, B.A., Donachy, J.E., Characterization of organic matrix macromolecules from the shells of the antarctic scallop Adamussium colbecki (1995) Comp. Biochem. Physiol., 111 B, pp. 221-231; Scott, J.E., Quintarelli, G., Dellovo, M.C., The chemical and histochemical properties of Alcian blue staining (1964) Histochemie, 4, pp. 73-85; Nakamoto, K., (1986) IR and Raman Spectra of Inorganic and Coordination Compounds, , J. Wiley & Sons, New York; Samata, T., Krampitz, G.P., Calcium binding polypeptides in oyster shells (1982) Malacologia, 22, pp. 225-233; Roeges, N.P.G., (1998) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , J. Wiley & Sons, New York; Cariolou, M., Morse, D., Purification and characterization of calcium binding conchiolin shell peptides from the mollusc, Haliotis rufescens, as a function of development (1988) J. Comp. Physiol., 157 B, pp. 717-729; Krampitz, G.P., Structure of the organic matrix in mollusc shells and avian eggshells (1982) Biological Mineralization and Demineralization, pp. 219-232. , Nancollas, G.H., ed. Springer-Verlag, Berlin, Heidelberg, New York; Weiner, S., Addadi, L., Acidic macromolecules of mineralized tissues: The controllers of crystal formation (1991) Trends Biochem. Sci., 16, pp. 252-256; Marin, F., Pereira, L., Westbroek, P., Large-scale fractionation of molluscan shell matrix (2001) Protein Expr. Purif., 23, pp. 175-179; Balmain, J., Hannoyer, B., Lopez, E., Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction analyses of mineral and organic matrix during heating of mother of pearl (nacre) from the shell of the mollusc Pinctada maxima (1999) J. Biomed. Mater. Res. Appl. Mat., 48, p. 754; Marxen, J.C., Hammer, M., Gehrke, T., Becker, W., Carbohydrates of the organic shell matrix and the shell forming tissue of the snail Biomphalaria glabrata (Say) (1998) Biol. Bull., 194, pp. 231-240; Miyazawa, T., Blout, E.R., The infrared spectra of polypeptides in various conformations - Amide I and II bands (1961) J. Am. Chem. Soc., 83, pp. 712-719; Worms, D., Weiner, S., Mollusk shell organic matrix: Fourier transform infrared study of the acidic macromolecules (1986) J. Exp. Zool., 237, pp. 11-20; Weiner, S., Traub, W., X-ray diffraction study of the insoluble organic matrix of mollusk shells (1980) FEBS Lett., 111, pp. 311-316; Pereira-Mouriès, L., Almeida, M.J., Marin, F., Gay, M., Milet, C., Lopez, E., Soluble proteins of the nacre from the giant oyster Pinctada maxima with highly hydrophobic amino acids (2002) Biomineralization: Formation, Diversity, Evol. Appl., , in press; Nakahara, H., Kakei, M., Bevelander, G., Fine structure and amino acid composition of the organic 'envelope' in the prismatic layer of some bivalve shells (1980) Venus Jpn. J. Malacol., 39, pp. 167-177; Falini, G., Albeck, S., Weiner, S., Addadi, L., Control of aragonite or calcite polymorphism by mollusk shell macromolecules (1996) Science, 271, pp. 67-69; Simkiss, K., The organic matrix of the oyster shell (1965) Comp. Biochem. Physiol., 16, pp. 427-435; Golberg, M., Takagi, M., Dentine proteoglycans: Composition, ultrastructure, and functions (1993) Histochem. J., 25, pp. 781-806; Wilbur, K.M., Recent studies of invertebrate mineralization (1976) The Mechanisms of Mineralization in Invertebrates and Plants, pp. 79-108. , Watabe, N. & Wilbur, K.M., eds. The University of South Carolina Press, The Belle W. Baruch Library in Marine Science no. 5, Columbia; Addadi, L., Moradian, J., Shay, E., Maroudas, N.G., Weiner, S., A chemical model for the cooperation of sulfates and carboxylates in calcite crystal nucleation: Revelance to biomineralization (1987) Proc. Natl. Acad. Sci. USA, 84, pp. 2732-2736; Marxen, J.C., Becker, W., Calcium binding constituents of the organic shell matrix from the freshwater snail Biomphalaria glabrata (2000) Comp. Biochem. Physiol., 127 B, pp. 235-242; Tanaka, Y., Adams, D.H., Shaw, S., Proteoglycans on endothelial cells present adhesion-inducing cytokines to leukocytes (1993) Immunol. Today, 14, pp. 111-115; Jackson, R.L., Bush, S.J., Cardin, A.D., Glycosaminoglycans: Molecular properties, protein interactions, and role in physiological processes (1991) Physiol. Rev., 71, pp. 481-539; Nakahara, H., Calcification of gastropod nacre (1983) Biomineralization and Biological Metal Accumulation, pp. 225-230. , Westbroek, P. & deJong, E.W., eds. Reidel, Dordrecht, Holland; Zentz, F., Bédouet, L., Almeida, M.J., Milet, C., Lopez, E., Giraud, M., Characterization and quantification of chitosan extracted from nacre of the abalone Haliotis tuberculata and the oyster Pinctada maxima (2001) Mar. Biotechnol., 3, pp. 36-44; Alzieu, C., Thibaud, Y., Heral, M., Boutier, B., Evaluation des risques dus a l'emploi des peintures anti-sallissures dans les zones conchyoliques (1980) Rev. Trav. Inst. Pêches Marit., 44, pp. 301-348; Alzieu, C., Heral, M., Thibaud, Y., Dardignac, M.J., Feuillet, M., Influence des peintures anti-sallissures à base d'organostanniques sur la calcification de la coquille de l'huître Crassostrea gigas (1982) Rev. Trav. Inst. Pêches Marit., 45, pp. 101-116; Krampitz, G., Drolshagen, H., Deltreil, J.P., Soluble matrix components in malformed oyster shells (1983) Experientia, 39, pp. 1105-1106; Alzieu, C., Heral, M., Ecotoxicological effects of organotin coumpounds on oyster culture (1984) Ecotoxicological Testing for the Marine Environment, 2, pp. 187-196. , Persoone, G., Jaspers, E. & Claus, C., eds. State University Ghent and Inst. Mar. Sci. Res., Bredene, Belgium; Almeida, M.J., (1996) Crescimento em Ostras: Factores que Afectam a Formação e Estrutura da Concha, , PhD Thesis, Instituto de Ciências Biomédicas Abel Salazar, University of Porto, Portugal; Sudo, S., Fujikawa, T., Nagakura, T., Ohkubo, T., Sakaguchi, K., Tanaka, M., Nakashina, K., Takahashi, T., Structures of mollusc shell framework proteins (1997) Nature, 387, pp. 563-564; Shen, X., Belcher, A.M., Hansma, P.K., Stucky, G.D., Morse, D.E., Molecular cloning and characterization of Lustrin A, a matrix protein from shell and pearl nacre of Haliotis rufescens (1997) J. Biol. Chem., 272, pp. 32472-32481; Samata, T., Hayashi, N., Kono, M., Hasegawa, K., Horita, C., Akera, S., A new matrix protein family related to the nacreous layer formation of Pinctada fucata (1999) FEBS Lett., 462, pp. 225-229; Mann, S., Webb, J., Williams, R.J.P., (1989) Biomineralization: Chemical and Biochemical Perspectives, pp. 35-62. , VCH, Weinheim; Simkiss, K., Wilbur, K.M., (1989) Biomineralization - Cell Biology and Mineral Deposition, , Academic Press, San Diego; Sarashina, I., Endo, K., Primary structure of a soluble matrix protein of scallop shell: Implications for calcium carbonate biomineralization (1998) Am. Mineral., 83, pp. 1510-1515; Weiss, I., Kaufmann, S., Mann, K., Fritz, M., Purification and characterization of perlucin and perlustrin, two new proteins from the shell of the mollusc Haliotis laevigata (2000) Biochem. Biophys. Res. Commun., 267, pp. 17-21; Pereira-Mouriès, L., Milet, C., Almeida, M.J., Rousseau, M., Borzeix, S., Lopez, E., Biological effect of the water-soluble matrix extract of the nacre shell layer of Pinctada maxima on vertebrate cell proliferation and differentiation (2001) Proceedings of the 3rd International Satellite Symposium on the Comparative Endocrinology of Calcium Regulation, , http://www.sci.port.ac.uk/-cecr, Gay, C.V., Dacke, C.G., Dancks, J.A. & Cox, P.A., eds; Pereira-Mouriès, L., Almeida, M.J., Milet, C., Berland, S., Lopez, E., Bioactivity of nacre water-soluble organic matrix from the bivalve mollusk Pinctada maxima in three mammalian cell types: Fibroblasts, bone marrow stromal cells and osteoblasts (2002) Comp. Biochem. Physiol., 132, pp. 215-217
Keywords: amino acid analysis; Amino acids; Animals; anion exchange chromatography; article; Biochemistry; biomineralization; bivalve; Bivalvia; Calcium; Chemical Fractionation; Chromatography, High Pressure Liquid; controlled study; demineralization; edetic acid; EDTA-soluble matrix; Electrophoresis, Polyacrylamide Gel; Extracellular Matrix Proteins; extraction; fractionation; gel permeation chromatography; glycosaminoglycan; Glycosaminoglycans; High performance liquid chromatography; hydrophobicity; infrared spectroscopy; Insect Proteins; model; Nacre; nonhuman; Ostreidae; Pinctada; Pinctada maxima; polyacrylamide gel electrophoresis; priority journal; Silk; Silk-fibroin-like-proteins; Solubility; Spectroscopy, Fourier Transform Infrared; Undecalcified soluble matrix; Water

Structural analysis of Si-substituted hydroxyapatite: Zeta potential and X-ray photoelectron spectroscopy - Botelho, C.M.; Lopes, M.A.; Gibson, I.R.; Best, S.M.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2002)
The aim of this study was to determine the effect of the incorporation of silicon on the surface charge of hydroxyapatite (HA) and to assess surface structural changes of HA and Si-HA induced by dissolution in both static and dynamic systems. X-ray photoelectron spectroscopy (XPS) analysis showed that SiO 4 4- groups were substituted for PO 4 3- groups in the silicon-hydroxyapatite (Si-HA) lattice according to a previously proposed substitution mechanism without the formation of other crystalline phases, such as tricalcium phosphate or calcium oxide. The substituted silicon induced a decrease in the net surface charge and the isoelectric point of HA as determined by zeta potential (ZP) measurements. At physiological pH = 7.4 the surface charge of Si-HA was significantly lowered compared to unmodified HA, i.e. -50 ±5 to - 71 ± 5 eV, caused by the presence of silicate groups in the HA lattice, which may account for a faster in vitro apatite formation using SBF testing. XPS results indicated that silicon seems to be preferentially leached out from Si-HA surface compared to other ionic species after dissolution studies in tris-buffer using a dynamic system. © 2002 Kluwer Academic Publishers.
Cited By (since 1996): 59Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1021177601899Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB - Inst. de Engenharia Biomedica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium oxide, 1305-78-8; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; phosphate, 14066-19-4, 14265-44-2; silicon, 7440-21-3Tradenames: Philips PW1606 spectrometer, Philips; Siemens D5000 X ray diffractometer, Siemens; Sotax CE6Manufacturers: Philips; SiemensReferences: Carlisle, E.M., (1984) Fed. Proc., 43, p. 680;Carlisle, E.M., (1986) Silicon Biochemistry, , edited by D. Evered and M. O'Connor (Wiley, New York); Schwarz, K., (1978) Biochemistry of Silicon and Related Problems, pp. 207-230. , edited by G. Bendz and I. Lindqvist (Plenum Press, New York); Schwarz, K., Milne, D.B., (1972) Nature, 239, p. 333; Voronkov, M.G., Skorobogatova, V.I., Vugmeister, E.K., Makarskii, V., (1975) Doklady Biochemistry, 222, p. 29; Hench, L.L., (1999) Biological Implications, pp. 116-163; Keeting, P.E., Oursler, M.J., Weigand, K.E., Bonds, S.K., Spelsberg, T.S., Riggs, B.L., (1992) J. Bone Mineral Res., 7, p. 1281; Hench, L.L., (1982) J. Phys., 43, p. 625; Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487; Hench, L.L., Wilson, J., (1999) An Introduction to Bioceramics, , World Scientific Publishing Co., Singapore; Jha, L.J., Best, S., Santos, J.D., Gibson, I.R., Bonfield, W., Silicon-Substituted Apatites and Process for the Preparation Thereof, , Worldwide Patent, PCT/GB97/02325 and US Patent Serial No 09/147773 (1999); Gibson, I.R., Best, S.M., Bonfield, W., (1999) J. Biomed. Mat. Res., 44, p. 422; Gibson, I.R., Huang, J., Best, S.M., Bonfield, W., (1999) Bioceramics, Vol. 12, Proceedings of the 12th International Symposium on Ceramics in Medicine (Nara, Japan November 1999), 12, pp. 191-194. , edited by H. Ohgushi, G. W. Hastings and T. Yoshikawa (World Scientific Publishing Co., London); Gibson, I.R., Hing, K.A., Revell, P.A., Santos, J.D., Best, S.M., Bonfield, W., (2002) Key Engin. Mat., 218-222, p. 203; Maroudas, N.G., (1975) J. Theoret. Biol., 49, p. 417; Van Wachem, P.B., Hogt, A.H., Beueling, T., (1987) Biomaterials, 8, p. 323; Davies, J.E., (1998) Surface Characterization of Biomaterials, pp. 219-234. , edited by B. D. Ratner (Elsevier, Amsterdam); Shelton, R.M., Rasmussen, A.C., Davies, J.E., (1988) Biomaterials, 9, p. 24; Ducheyne, P., Beight, J., Cuckler, J., Evans, B., Radin, S., (1990) Biomaterials, 11, p. 531; Ohgushi, H., Goldberg, V.M., Caplan, A.I., (1989) J. Orthop. Res., 7, p. 568; Daculsi, G., Le Geros, R.Z., Nery, E., Lynch, K., Kerebel, B., (1989) J. Biomed. Mater. Res., 23, p. 883; Hyakuna, K., Yamamuro, T., Kotoura, Y., Kakutani, Y., Kitsugi, T., Takagi, H., Oka, M., Kokubo, T., (1989) J. Biomed. Mater. Res., 23, p. 1049; Kotoura, Y., Yamamuro, T., Shikata, J., Kakutani, Y., Kitsugi, T., Hyakuna, K., Tanaka, H., (1986) Orthop. Res. Sci., 13, p. 633; Fujiu, T., Ogino, M., (1984) J. Biomed. Mater. Res., 18, p. 845; Rehman, I., Bonfield, W., (1997) J. Mat. Sci.: Mater. in Med., 8, p. 1; Nyquist, R.A., Putzig, C.L., Leugers, M.A., (1995) Infrared and Raman Spectral Atlas of Inorganic Compounds and Organic Salts, 3; NIST - National Institute of Standards and Technology Database; Van Raemdonck, W., Ducheyne, P., De Meester, P., (1984) Metal and Ceramic Biomaterials, pp. 143-146. , CRC Press; Gibson, I.R., Jha, L.J., Santos, J.D., Best, S.M., Bonfield, W., (1998) Bioceramics, Vol. 11, Proceedings of the 11th International Symposium on Ceramics in Medicine (New York, NY, USA, November 1998), , edited by R. Z. LeGeros and J. P. LeGeros (World Scientific Publishing Co., USA)
Keywords: calcium oxide; calcium phosphate; Chemical modification; conference paper; crystal structure; Dissolution; Electric Potential; electricity; hydroxyapatite; in vitro study; isoelectric point; Lime; molecular dynamics; pH; pH measurement; phase transition; phosphate; Phosphorus Compounds; priority journal; reaction analysis; Silicon; Silicon compounds; silicon derivative; structure analysis; surface property; X ray photoelectron spectroscopy; Zeta potential

Wettability and surface charge of Si 3N 4-bioglass composites in contact with simulated physiological liquids - Amaral, M.; Lopes, M.A.; Santos, J.D.; Silva, R.F. (BiomaterialsBiomaterials, 2002)
Wettability and surface charge studies were performed on a novel Si 3N 4-30wt% bioglass biocomposite. Contact angle and surface tension variation with time were determined at 25°C, respectively, by the sessile and pendant drop techniques, for distinct testing liquids: water, diiodomethane, simulated body fluid (SBF) and bovine serum albumin (BSA) dissolved in SBF solution. This biocomposite revealed a hydrophilic character (θ=26.6±2.0°) and a surface tension value (66.6mJm
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00155-2Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Inst. de Engenharia Biomedica (INEB), Rua do Campo Alegre, 823, 4150 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Serum Albumin, Bovine; Silicon Compounds; silicon nitride, 12033-89-5References: Von Recum, A.F., (1999) Handbook of biomaterials evaluation: scientific, technical, and clinical testing of implant materials, 2nd. ed., , Hemisphere Pub;Davies, J.E., The importance and measurement of surface charge species in cell behaviour at the biomaterial interface (1998) Surface characterisation of biomaterials, 6, pp. 219-234. , Ratner, editor. Progress in Biomedical Engineering. Amsterdam: Elsevier; Lampin, M., Warocquier-Clérout, R., Legris, C., Degrange, M., Sigot-Luizard, M.F., Correlation between substratum roughness and wettability, cell adhesion, and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Dewez, J.L., Schneider, Y.J., Rouxhet, P.G., Coupled influence of substratum hydrophilicity and surfactant on epithelial cell adhesion (1996) J Biomed Mater Res, 30, pp. 373-383; Hallab, N.J., Bundy, K., O'Connor, R., Clark, R., Moses, R.L., Cell adhesion to biomaterials: Correlations between surface charge, surface roughness, adsorbed protein, and cell morphology (1995) J Long-Term Effects Med Implants, 3, pp. 209-231; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 7, pp. 667-681; Garbassi, Morra, Occhiello, Polymer surfaces, from physics to technology, , Wiley & Sons, New York [Chapter 4]; Adamson, A.W., (1990) Physical chemistry of surfaces, , 5th ed, New York: Wiley; Correia, N.T., Ramos, J.M., Saramago, B., Calado, J., Estimation of the surface tension of a solid: Application to a liquid crystalline (1997) J Colloid Interface Sci, 189, pp. 361-369; Schrader, M.E., Young-Dupre Revisited (1995) Langmuir, 11, pp. 3585-3589; Nishizawa, K., Toriyama, M., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal-cells (1993) J Ferment Bioeng, 6, pp. 435-437; Suzuki, T., Nishizawa, K., Yokogawa, Y., Kameyama, T., Time-dependent variation of the surface structure of bioceramics in tissue culture medium and the effect on adhesiveness of cells (1996) J Ferment Bioeng, 3, pp. 226-232; Parfitt, G.D., (1967) Principles of the colloidal state, , London: Royal Institute of Chemistry; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si3N4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon nitride-bioglass ® composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Krajewski, A., Piancastelli, A., Malavolti, R., Albumin adhesion on ceramics and correlation with their Z-potential (1998) Biomaterials, 19, pp. 637-641; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J Mater Sci: Mater Med, 3, pp. 79-83; Vogler, E.A., Interfacial chemistry in biomaterials science (1993) Wettability, surfactant science series, 49, pp. 183-250. , Berg J.C., editor, Chapter 4; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., Effect of chemical composition on hydrophobicity and zeta potential of plasma sprayed HA/CaO-P 2O 5 glass coatings (2001) Biomaterials, 22, pp. 3105-3112; Agathopoulos, S., Nikolopoulos, P., Wettability and interfacial interactions in bioceramic-body-liquid systems (1995) J Biomed Mater Res, 29, pp. 421-429; Agathopoulos, S., Nikolopoulos, P., Determination of the energy of the interactions between oxides and biological liquids (1995) Fourth Euro ceramics, 8, pp. 319-324. , A. Ravaglioli; Wang, L., Sigmund, W., Aldinger, F., Systematic approach for dispersion of silicon nitride powder in organic media: I, surface chemistry of the powder (2000) J Am Ceram Soc, 4, pp. 691-696; Galassi, C., Bertoni, F., Water-based Si 3N 4 suspensions: Part I effect of processing routes on the surface chemistry and particle interactions (2000) J Mater Res, 1, pp. 155-163; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Colloids Surf B: Biointerfaces, 2, pp. 517-566
Keywords: 3N; 4-bioglass composites; Adsorption; aqueous solution; article; Biocomposites; Biomaterials; body fluid; Body fluids; Bovinae; bovine serum albumin; cation; Cattle; ceramics; chemistry; conformation; Conformations; Contact angle; electrochemistry; enthalpy; entropy; glass; Glass ceramics; Hydrogen-Ion Concentration; hydrophilicity; liquid; methyl iodide; methylene iodide; pH; Physiological models; priority journal; Serum Albumin; Serum Albumin, Bovine; Si; Silicon compounds; silicon derivative; Silicon nitride; simulation; Support, Non-U.S. Gov't; Surface charge; Surface chemistry; Surface Properties; surface property; Surface tension; temperature; time; unclassified drug; Water; wettability; Wetting; Zeta potential

Adsorption and release studies of sodium ampicillin from hydroxyapatite and glass-reinforced hydroxyapatite composites - Queiroz, A.C.; Santos, J.D.; Monteiro, F.J.; Gibson, I.R.; Knowles, J.C. (BiomaterialsBiomaterials, 2001)
As a potential therapy for periodontitis, sodium ampicillin, a broad spectrum antibiotic, was adsorbed onto hydroxyapatite (HA) and glass-reinforced hydroxyaptite (GR-HA) composites, and was subsequently released in vitro. The sodium ampicillin, was adsorbed more on HA compared to the GR-HA composites. X-ray diffraction (XRD) and Rietveld analysis were used to identify and quantify the levels of HA and β-tricalcium phosphate (β-TCP) in the microstructure of the GR-HA composites. Lattice parameters changes were observed for the β-TCP phase dependant on the amount of glass added. The release kinetics were shown to be divided into three stages, the first of which where a large amount of sodium ampicillin is released, followed by a slower release rate and then a final stage where the release amount approaches zero, until no more sodium ampicillin was present. X-ray photoeletron spectroscopy (XPS) studies were carried out in order to ensure that the entire antibiotic adsorbed onto the materials had been released. These kinetics studies have indicated the possibility of using these materials as possible carriers for drug delivery. Copyright © 2001 Elsevier Science Ltd.
Cited By (since 1996): 55Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00296-9PubMed ID: 11336313Language of Original Document: EnglishCorrespondence Address: Knowles, J.C.; Department of Biomaterials, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: j.knowles@eastman.ucl.ac.ukChemicals/CAS: Ampicillin, 69-53-4; Durapatite, 1306-06-5; PenicillinsManufacturers: Plasma Biotal, United KingdomReferences: Farag, S.A., Simultaneous liquid chromatographic analysis of the β-lactam antibiotics cefazolin, cefadroxil, cepalexin, ampicillin, and cephradine in solution (1998) J AOAC Int, 81, pp. 381-385;Somayaji, B.V., Jariwala, U., Jayachandran, P., Vidyalakshmi, K., Dudhani, R.V., Evaluation of antimicrobial efficacy and release pattern of tetracycline and metronidazole using a local delivery system (1998) J Periodontol, 69, pp. 409-413; Soskolne, W.A., Heasman, P.A., Stabholz, A., Smart, G.J., Palmer, M., Flashner, M., Newman, H.N., Sustained local delivery of chlorhexidine in the treatment of periodontitis; a multi-center study (1997) J Periodontol, 68, pp. 32-38; Steinberg, D., Friedman, M., Soskolne, A., Sela, M.N., A new degradable controlled release device for treatment of periodontal disease; in vitro release study (1990) J Periodontol, 61, pp. 393-398; Stoltze, K., Concentration of metronidazole in periodontal pockets after application of a metronidazole 25% dental gel (1992) J Clin Periodontol, 19, pp. 698-701; Ramaglia, L., Sbordone, L., Lenci, F., Gulletta, E., Amato, G., Kennedy, E.B., Microbiology of porous hydroxylapatite implants in human periodontal osseous defects (1986) Biomaterials and clinical applications, 7 vol., pp. 675-680. , Pizzoferrate A., Marachetti P.G., Ravaglioli A., Lee A.J.C. (Eds.), Netherlands: Elsevier; Wilson, J., Low, S., Fetner, A., Hench, L.L., Bioactive materials for periodontal treatment; a comparative study (1986) Biomaterials and clinical applications, 7 vol., pp. 223-228. , Pizzoferrate A., Marachetti P.G., Ravaglioli A., Lee A.J.C. (Eds.), Netherlands: Elsevier; Kenney, E.B., Lekovic, V., Sa Ferreira, J.C., Han, T., Dimitrijavic, B., Carranza F.A. Jr, Bone formation within porous hydroxyapatite implants in human periodontal defects (1986) J Periodontol, 57, pp. 76-83; Krejei, C.B., Bissada, N.F., Farah, C., Greenwell, H., Clinical evaluation of porous and nonporous hydroxyapatite in treatment of human periodontal bony defects (1987) J Periodontol, 58, pp. 521-528; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tensions, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Santos, J.D., Silva, P.L., Knowles, J.C., Talal, S., Monteiro, F.J., Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O, MgO (1996) J Mater Sci Mater Med, 7, pp. 187-189; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Osteocompatibility and in vivo evaluation of glass reinforced hydroxyapatite composites (1999) Bioceramics, 12 vol., pp. 421-424. , Ohgushi H., Hastings G.W., Yoshikawa T. (Eds.), Japan: World Scientific; Santos, J.D., Vasconcelos, M., Reis, R.L., Afonso, A., Monteiro, F.J., Hastings, G.W., Glass reinforced hydroxyapatite composites; physical properties and preliminary histological studies in rabbits (1994) Bioceramics, 7 vol., pp. 243-248. , Andersson O.H., Yli-Urpo A. (Eds.), Finland: Pergamon Press; Klein, C.P.A.T., Wolke, J.G.C., de Blieck-Hogervorst, J.M.A., de Groot, K., Features of calcium phosphate plasma-sprayed coatings; an in vitro study (1994) J Biomed Mater Res, 28, pp. 961-967; Klein, C.P.A.T., Wolke, J.G.C., de Blieck-Hogervorst, J.M.A., de Groot, K., Calcium phosphate plasma-sprayed coatings and their stability; an in vivo study (1994) J Biomed Mater Res, 28, pp. 909-917; Langnbucher, F., Benz, D., Kürth, W., Möller, H., Otz, M., Standardized Flow-cell method as an alternative to existing pharmacopoeial dissolution testing (1989) Pharm Ind, 51, pp. 1276-1281; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite; a comprehensive study of the effect of glass composition on crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Thomas M. Ultraviolet and visible spectroscopy, second edition. In: Ando DJ, editor. England: Wiley, 1996. p. 16-30Itokazu, M., Itoh, Y., Fukuta, M., Miyamato, K., Ohara, A., Oshima, K., Nishimoto, Y., Shimizu, K., Treatment of osteomyelitis by using antibiotic loaded porous ceramic (1999) Bioceramics, 12 vol., pp. 3-6. , Ohgushi H., Hastings G.W., Yoshikawa T. (Eds.), Japan: World Scientific; Shinto, Y., Uchida, A., Korkusuz, F., Araki, N., Ono, K., Calcium hydroxyapatite ceramic used as a delivery system for antibiotics (1992) J Bone Jt Surg, 74 B, pp. 600-604; Downes, S., Clifford, C.J., Scotchford, C., Klein, C.P.A.T., Comparison of the release of growth hormone from hydroxyapatite, heat-treated hydroxyapatite, and fluoroapatite coatings on titanium (1995) J Biomed Mater Res, 29, pp. 1053-1060; Curtis, M.A., Griffiths, G.S., Johnson, N.W., The total protein concentration of gingival crevicular fluid. Variation with sampling time and gingival inflammation (1988) J Clin Periondontol, 15, pp. 628-632; Stoltze K. Concentration of metronidazole in periodontal pockets after application of a metronidazole 25% dental gel. J Clin Periondontol 1992, 689-701Jones, A.A., Koenman, K.S., Newbold, D.A., Manwell, M.A., Clinical and microbiological effects of controlled release locally delivered minocycline in periodontitis (1994) J Periodontol, 65, pp. 1058-1066
Keywords: Adsorption; ampicillin; Antibiotics; article; calcium phosphate; composite material; controlled study; drug adsorption; Drug delivery; drug delivery system; Drug release; Durapatite; glass; Glass-reinforced hydroxyapatite; hydroxyapatite; Kinetics; Microstructure; Penicillins; periodontitis; priority journal; Reinforcement; Rietveld analysis; roentgen spectroscopy; Sodium ampicillin; Sodium compounds; structure analysis; unclassified drug; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

Affinity of hydroxyapatite to metal cations - a study on the composition and structure of phosphates formed in the presence of titanium and aluminum - Ribeiro, C.C.; Barbosa, M.A. (Key Engineering MaterialsKey Eng Mat, 2001)
The purpose of this study was to contribute to the understanding of the effect of titanium, aluminium and titanium/aluminium on the Hap structure and to investigate if a synergistic effect between the two cations exists. The effect of the metal ion concentration was studied. The solids were analysed by X-ray diffraction, Fourier transform infrared spectroscopy, FT-Raman spectroscopy and energy dispersive X-ray analysis.
Conference code: 57760Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Ribeiro, C.C.; INEB, Porto, PortugalReferences: Andress, D.L., Maloney, N.A., Endres, D.B., Sherrard, D.J., (1986) J. Bone Mineral Res., 1, p. 391;Posner, A.S., Blumenthal, N.C., Boskey, A.L., (1986) Kidney Int., 29, p. 17; Christoffersen, M.R., Christoffersen, J., (1985) J. Calcif. Tissue Int., 37, p. 673; Christoffersen, M.R., Thyregod, H.C., Christoffersen, J., (1987) J. Calcif. Tissue Int., 41, p. 27; Blumenthal, N.C., Cosma, V., (1989) J. Biomed. Mater. Res., 23, p. 13; Gerber, H., Perren, S.M., (1980) Evaluation of Biomaterials, p. 307. , Wiley-Chichester, England; Ribeiro, C.C., Barbosa, M.A., (1995) J. of Mat. Science: Mat. in Med., 6, p. 829
Keywords: Aluminum; Energy dispersive spectroscopy; Fourier transform infrared spectroscopy; Hap structure; hydroxyapatite; Positive ions; Raman spectroscopy; Structure (composition); Synergistic effect; Titanium; X ray diffraction analysis

CaO-P 2O 5 glass ceramics containing bioactive phases: crystallisation and in vitro bioactivity studies - Zhang, Y.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2001)
CaO-P 2O 5 glass ceramics were prepared using a two-step heat treatment of nucleation and crystal growth using TiO 2 and Na 2O as nucleating agents. X-ray diffraction analysis demonstrated that bioactive and bioresorbable crystalline phases were precipitated in the microstructure, depending upon the relative content of the additives and of the CaO/P 2O 5 ratio of the glass. Ca 2P 2O 7 (β-DCP) was the main crystalline phase however β-Ca 3(PO 4) 2 (β-TCP), could also be formed by increasing the content of TiO 2 and the CaO/P 2O 5 ratio. Na and Ti-containing phases, CaTi 4(PO 4) 6, and/or NaTi 2(PO 4) 3, could also be assigned in the XRD spectra. In vitro testing in simulated body fluid (SBF) has proved the in vitro bioactivity of these glass ceramics with the formation of Ca-deficient apatite crystals, as demonstrated by Scanning Electron Microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) analyses.
Conference code: 57760Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Zhang, Y.; Instituto de Engenharia Biomedica, (INEB), Porto, PortugalReferences: Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487;Kokubo, T., (1993) An Introduction to Bioceramics, p. 75. , L.L. Hench and J.Wilson, Eds., World Scientific Singapore; Abe, Y., Naruse, A., Hosoe, M., Fukui, H., Hasegawa, J., (1975) The 1975 Symposium of Biomaterials, p. 202. , Kyoto; Reaney, I.M., James, P.F., Lee, W.E., (1996) J. Am. Ceram. Soc., Science, 79, pp. 1934-1944; Kasuga, T., Abe, Y., (1998) J. Mater. Res., 13, p. 1; Vogel, J., Schulze, K.J., Reif, D., Hartmann, P., Platzbecker, U., Leuner, B., (1997) Bioceramics, 10, p. 57. , L. Sedel and C. Rey, Eds., Elsevier Science; Hosono, H., Zhang, Z., Abe, Y., (1989) J. Am. Ceram. Soc., 72, p. 1587; Zhang, Y., Santos, J.D., Journal of the European Ceramic Society, , In press
Keywords: Bioactivity; Biomaterials; Ceramic materials; Crystal growth; Crystal microstructure; Crystalline materials; Crystalline phase; Crystallization; glass; Lime; Nucleating agents; Nucleation; Phosphates; Scanning electron microscopy; Simulated body fluid; X ray diffraction analysis; X ray photoelectron spectroscopy

Cellulose phosphates as biomaterials. I. Synthesis and characterization of highly phosphorylated cellulose gels - Granja, P.L.; Pouysgu, L.; Ptraud, M.; De Jso, B.; Baquey, C.; Barbosa, M.A. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 2001)
The present study concerns the investigation of a material expected to be biocompatible and able to promote bone regeneration. For this purpose, cellulose was chemically modified by phosphorylation. Once implanted, phosphorylated cellulose could promote the formation of calcium phosphates, thus having closer resemblance to bone functionality. In a previous investigation, the obtention and the preliminary characterization of cellulose phosphate gels were reported. In the present study, the synthesis by the H 3PO 4/P 2O 5/Et 3PO 4/hexanol method was optimized in terms of reaction parameters. The structure of materials was investigated by FTIR, Raman, and solid-state 31P- and 13C-NMR spectroscopic studies, and X-ray diffraction. Water swelling and stability to sterilization by gamma-radiation were also assessed. It was demonstrated that the present method allows highly phosphorylated cellulose derivatives to be obtained. Cellulose triphosphates gels are described here for the first time. Products obtained were poorly crystallized monoesters, apparently not significantly affected by gamma sterilization and showed a high water swelling capability. Chemical bonding was confirmed by FTIR, Raman, and both 31P- and 13C-NMR spectroscopies. It was also shown that the H 3PO 4/P 2O 5/Et 3PO 4/hexanol method provides a versatile and interesting alternative route to some of the more widely used techniques for the phosphorylation of cellulose. © 2001 John Wiley & Sons, Inc. J. Appl. Polym. Sci.
Cited By (since 1996): 27Export Date: 21 November 2012Source: ScopusCODEN: JAPNAdoi: 10.1002/app.2193Language of Original Document: EnglishCorrespondence Address: Granja, P.L.; Laboratório de Biomateriais, Instituto de Engenharia Biomedica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: pgranja@ibmc.up.ptReferences: Dumitriu, S., (1996) Polysaccharides in Medical Applications, , Marcel Dekker: New York;Franz, G., (1986) Adv Polym Sci, 76, p. 1; Ikada, Y., (1989) Cellulose: Structural and Functional Aspects, p. 447. , Kennedy J. F.; Phillips, G. O.; Williams, P. A., Eds.; Ellis Horwood: Chichester, UK, Chapter 59; Galleti, P.M., Colton, C.K., Lysaght, M.J., (1995) The Biomedical Engineering Handbook, p. 1898. , Bronzino, J. D., Ed.; CRC Press: Boca Raton, FL, Chapter 126; Hon, D.N.-S., (1996) Polysaccharides in Medicinal Applications, p. 87. , Dumitriu, S., Ed.; Marcel Dekker: New York, Chapter 4; Doelker, E., (1993) Adv Polym Sci, 107, p. 199; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., Noishiki, Y., (1989) J Biomed Mater Res, 23, p. 125; Okajima, K., (1989) Cellulose: Structural and Functional Aspects, p. 439. , Kennedy, J. F.; Phillips, G. O.; Williams, P. A., Eds.; Ellis Horwood: Chichester, UK ; Chapter 58; Ahlgren, P., (1995) Nord Pulp Paper Res J, 1, p. 12; Dimemmo, L.M., Falkiewicz, M.J., (1985) Cellulose and Its Derivatives: Chemistry, Biochemistry and Applications, p. 511. , Kennedy, J. F.; Phillips, G. O.; Wedlock, D. J.; Williams, P. A., Eds.; Ellis Horwood: Chichester, UK, Chapter 47; Ross-Murphy, S.B., (1985) Cellulose Chemistry and Its Applications, p. 202. , Nevell, T. P.; Zeronian, S. H., Eds.; Ellis Horwood: Chichester, UK, Chapter 8; Steege, H., Philipp, B., Engst, R., Magister, G., Lewerenz, H.J., Bleyl, D., (1978) Tappi, 61, p. 101; Battista, O.A., (1971) Cellulose and Cellulose Derivatives (Part V), 5, p. 1265. , Bikales, N. M.; Segal, L., Eds.; High Polymers series, Wiley-Interscience: New York, Chapter 19; Matthew, I.R., Browne, R.M., Frame, J.W., Millar, B.G., (1995) Biomaterials, 16, p. 275; Finn, M.D., Schow, S.R., Schneiderman, E.D., (1992) J Oral Maxillofac Surg, 50, p. 608; Galgut, P.N., (1990) Biomaterials, 11, p. 561; Martson, M., Viljanto, J., Hurme, T., Laippala, P., Saukko, P., (1999) Biomaterials, 20, p. 1899; Poustis, J., Baquey, C., Chauveaux, D., (1994) Clin Mater, 16, p. 119; Gross, U., Müller-Mai, C., Voigt, C., The tissue response on cellulose cylinders after implantation in the distal femur of rabbits (1992) Proceedings of the 4th World Biomaterials Congress, p. 192. , Berlin, Germany, April; Baquey, C., Barbié, C., More, N., Rouais, F., Poustis, J., Chauveaux, D., (1992) Proceedings of the 4th World Biomaterials Congress, p. 365. , In vivo study of the biostability of a cellulose material, Berlin, Germany, April; Chauveaux, D., Barbié, C., Barthe, X., Baquey, C., (1990) Poustis, J Clin Mater, 5, p. 251; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D.Fr., Demande 8610331, 1986; Eur. Pat. 0256906 Al, 1987; U.S. Pat. 4,904,258, 1990Mizusawa, Y., Burke, J.R., (1996) J Pediatr Child Health, 32, p. 350; Parfitt, A.M., (1975) Clin Sci Mol Med, 49, p. 83; Pak, C.Y.C., Delea, C.S., Bartter, F.C., (1974) N Engl J Med, 290, p. 175; Dowd, V., Yon, R.J., (1992) J Chromatogr, 627, p. 145; Ermolenko, I.N., Lyubliner, I.P., Borodin, I.F., Orlyanskaya, V.F., Gavrilova, A.A., (1984) USSR Otkrytiya Izobret, p. 17; Sugihara, J., Imamura, T., Yanase, T., (1982) J Chromatogr, 229, p. 193; Longin, M.L., Buglov, E.D., Ermolenko, I.N., (1975) Vestsi Akad Navuk B SSR Ser Khim Navuk, p. 82; Shih, T.Y., Martin, M.A., (1974) Biochemistry, 13, p. 3411; Antonova, E.V., Mikhnovich, E.P., Shulutko, L.S., (1972) Probl Gematol Pereliv Krovi, 17, p. 25; Ermolenko, I.N., Lyubliner, I.P., (1971) Khim Teknhol Proizvod Tsellyul, p. 337; Holmquist, W.R., Schroeder, W.A., (1967) J Chromatogr, 26, p. 465; Kotake, Y., Ida, K., Kondo, S., Jpn. Pat. 10947(56), 1958Yokogawa, Y., Paz Reyes, J., Mucalo, M.R., Toriyama, M., Kawamoto, Y., Suzuki, T., Nishizawa, K., Kamayama, T., (1997) J Mater Sci Mater Med, 8, p. 407; Kato, E., Eika, Y., Ikada, Y., (1996) J Biomed Mater Res, 32, p. 687; Tretinnikov, O.N., Kato, K., Ikada, Y., (1994) J Biomed Mater Res, 28, p. 1365; Dalas, E., Kallistis, J., Koutsoukos, P.G., (1991) Langmuir, 7, p. 1822; Li, S., Liu, Q., De Wijn, J., Wolke, J., Zhou, B., De Groot, K., (1997) J Mater Sci Mater Mod, 8, p. 543; Mucalo, M.R., Yokogawa, Y., Toriyama, M., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., (1995) J Mater Sci Mater Med, 6, p. 597; Mucalo, M.R., Yokogawa, Y., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., (1995) J Mater Sci Mater Mod, 6, p. 658; Klemm, D., Philipp, B., Heinze, T., Heinze, U., Wagenknecht, W., (1998) Comprehensive Cellulose Chemistry: Functionalization of Cellulose, 2, p. 133. , Wiley-VCH Verlag: Weinheim, Germany, Chapter 4; Ishizu, A., (1991) Wood and Cellulose Chemistry, p. 757. , Hon, D. N.-S.; Shiraishi, N., Eds.; Marcel Dekker: New York, Chapter 16; Woodsworth, L.C., Daponte, D., (1985) Cellulose Chemistry and Applications, p. 344. , Nevell T. P.; Zeronian, S. H., Eds.; Ellis Horwood: Chichester, UK, Chapter 14; Reid, J.D., Mazzeno L.W., Jr., (1949) Ind Eng Chem, 41, p. 2828; Granja, P.L., Barbosa, M.A., Pouységu, L., De Jéso, B., Baquey, C., (1999) Frontiers in Biomedical Polymers Applications, 2, p. 195. , Ottenbrite, R., Ed.; Technomic Press: Lancaster, PA; Granja, P.L., Baquey, C., Pouységu, L., Bareille, R., De Jéso, B., Barbosa, M.A., (1996) Polymers in Medicine and Surgery (PIMS'96), p. 73. , Glasgow, UK; Touey, G.P., Kingsport, T., U.S. Pat. 2,759,924, 1956Inoue, H., Baba, Y., Tsuhako, M., (1995) Chem Pharm Bull, 43, p. 677; Quin, L.D., Jankowski, S., WO 1994, 94/02226Wagenknecht, W., Nehls, I., Philipp, B., Schnabelrauch, M., Klemm, D., Hartmann, M., (1991) Acta Polym, 42, p. 554; Slotin, L.A., (1977) Synthesis, p. 737. , November; Inagaki, N., Nakamura, S., Asai, H., Katsuura, K., (1976) J Appl Polym Sci, 20, p. 2829; Vigo, T.L., Welch, C.M., (1974) Carbohydr Res, 32, p. 331; Towle, G.A., Whistler, R.L., (1972) Methods in Carbohydrate Chemistry, 6, p. 408. , Whistler, R. L., Ed.; Academic Press: New York ; Chapter 75; Katsuura, K., Nonaka, S., (1957) Sen-i-Gakkaishi, 13, p. 24; Nuessle, A.C., Ford, F.M., Hall, W.P., Lippert, A.L., (1956) Text Res J, 26, p. 32; Bertran, M.S., Dale, B.E., (1986) J Appl Polym Sci, 32, p. 4241; Reid, J.D., Mazzeno L.W., Jr., (1949) Ind Eng Chem, 41, p. 2831; (1982) Essais des eaux: Dosage des orthophosphates, des polyphosphates et du phosphore total (Méthode spectrométrique), , AFNOR: Saint-Denis La Plaine, NF T 90-023; Segal, L., Creely, J.J., Martin A.E., Jr., Conrad, C.M., (1959) Text Res J, 29, p. 786; Nelson, M.L., O'Connor, R.T., (1964) J Appl Polym Sci, 8, p. 1325; Klemm, D., Philipp, B., Heinze, T., Heinze, U., Wagenknecht, W., (1998) Comprehensive Cellulose Chemistry: Fundamentals and Analytical Methods, 1, p. 9. , Wiley-VCH Verlag: Weinheim, Germany, Chapter 2; Zeronian, S.H., (1985) Cellulose Chemistry and Its Applications, p. 159. , Novell, T. P.; Zeronian, S. H., Eds.; Ellis Horwood: Chichester, UK, Chapter 6; Klemm, D., Philipp, B., Heinze, T., Heinze, U., Wagenknecht, W., (1998) Comprehensive Cellulose Chemistry: Fundamentals and Analytical Methods, 1, p. 181. , Wiley-VCH Verlag: Weinheim, Germany, Chapter 3; Nyquist, R.A., Craver, C.D., (1977) The Coblentz Society Desk Book of Infrared Spectra, p. 399. , Craver C. D., Ed.; The Coblentz Society: French Village, MO; Nakamoto, K., (1977) Infrared and Raman Spectra of Inorganic and Coordination Compounds, 3rd ed., , Wiley-Interscience: New York; Kuptsov, A.H., Zhizhin, G.N., (1998) Handbook of fourier transform raman and infrared spectra of polymers, Physical Series Data, 45. , Elsevier: Amsterdam; Blackwell, J., (1977) ACS Symp Ser, 48, p. 206; Matthews, I.P., Gibson, C., Samuel, A.H., (1994) Clin Mater, 15, p. 191; Chamberlain, V.C., Lambert, B., Tang, F.-W., (1999) Handbook of Biomaterials Evaluation: Scientific, Technical, and Clinical Testing of Implant Materials, p. 253. , von Recum, A. F., Ed.; Taylor & Francis: Philadelphia Chapter 15; Ahmed, A.U., Rapson, W.H., (1972) J Polym Sci Part A Polym Chem, 10, p. 1945; Phillips, G.O., Arthur J.C., Jr., (1985) Cellulose Chemistry and Its Applications, p. 290. , Novell, T. P.; Zeronian, S. H., Eds.; Ellis Horwood: Chichester, UK, Chapter 12; Larsson, P.T., Wickholm, K., Iversen, T., (1997) Carbohydr Res, 302, p. 19; Lai, Y.-Z., (1996) Chemical Modification of Lignocellulosic Materials, p. 35. , Hon, D. N.-S., Ed.; Marcel Dekker: New York, Chapter 3; Schultz, T.P., McGinnis, G.D., Bertran, M.S., (1985) J Wood Chem Technol, 5, p. 543; Roberts, G.A.F., (1992) Paper Chemistry, p. 9. , Roberts, J. C., Ed.; Blackie Academic & Professional: Glasgow/London, Chapter 2; El-Saied, H., Hanna, A.A., Ibrahem, A.A., (1985) Indian Pulp Paper, 7-10, p. 24; Canet, D., (1996) Nuclear Magnetic Resonance: Concepts and Methods, , Wiley: Chichester, UK; Wu, Y., Glimcher, M.J., Rey, C., Ackerman, J.L., (1994) J Mol Biol, 244, p. 423; Sabesan, S., Neira, S., (1992) Carbohydr Res, 223, p. 169; Nehls, I., Loth, F., (1991) Acta Polym, 42, p. 233; Nehls, I., Wagenknecht, W., Philipp, B., Stscherbina, D., (1994) Prog Polym Sci, 19, p. 29; Buchanan, G.W., Preusser, S.H., Webb, V.L., (1984) Can J Chem, 62, p. 1308; Christofides, J.C., Davies, D.B., (1983) J Am Chem Soc, 105, p. 5099; Beierbeck, H., Saunders, J.K., (1976) Can J Chem, 54, p. 2985; Powlowski, W.P., (1987) J Macromol Sci Chem, 25, p. 3355; Lowman, D.W., (1998) Cellulose Derivatives: Modification, Characterization, and Nanostructures, p. 131. , Heinze, T. J.; Glasser, W. G., Eds.; ACS Symposium Series 688; American Chemical Society: Washington, DC, Chapter 10; Nehls, I., Wagenknecht, W., Philipp, B., (1995) Cellul Chem Technol, 29, p. 243; Nehls, I., Philipp, B., Wagenknecht, W., (1995) Cellulose and Cellulose Derivatives: Physico-Chemical Aspects and Industrial Applications, p. 153. , Kennedy, J. F.; Phillips, G. O.; Williams, P. A., Eds.; Woodhead Publishing: Cambridge, UK, Chapter 20; Hoshino, M., Takai, M., Fukuda, K., Imura, K., Hayashi, J., (1989) J Polym Sci Part A Polym Chem, 27, p. 2083; Takahashi, S.I., Fujimoto, T., Barua, B.M., Miyamoto, T., Inagaki, H., (1986) J Polym Sci Part A Polym Chem, 24, p. 2981; Miyamoto, T., Sato, Y., Shibata, T., Inagaki, H., Tanahashi, M., (1984) J Polym Sci Part A Polym Chem, 22, p. 2363; VanderHart, D.L., Hyatt, J.A., Atalla, R.H., Tirumalai, V.C., (1996) Macromolecules, 29, p. 730; Horii, F., Hirai, F., Kitamaru, R., (1992) Polym Bull, 8, p. 163; Atalla, R.H., VanderHart, D.L., (1984) Science, 223, p. 283; Ganapathy, S., Badiger, M.V., Rajamohanan, P.R., Mashelkar, R.A., (1992) Macromolecules, 25, p. 4255; Horii, F., (1989) Nuclear Magnetic Resonance in Agriculture, p. 311. , Pfeffer, P. E.; Gerasimovicz, W. V., Eds.; CRC Press: Boca Raton, FL; Horii, F., Hirai, A., Kitamaru, R., (1986) Macromolecules, 19, p. 930; Okada, K., Yokogawa, Y., Kameyama, T., Kato, K., Kawamoto, Y., Nishizawa, K., Nagata, F., Okuyama, M., (1997) Bioceramics, 10, p. 329. , Sedel, L.; Rey, C., Eds.; Elsevier: Amsterdam; Yalpani, M., (1992) Carbohydr Polym, 19, p. 35; Nishi, N., Ebina, A., Nishimura, S., Tsutsumi, A., Hasegawa, O., Tokura, S., (1986) Int J Biol Macromol, 8, p. 311
Keywords: 13C-NMR; 2O; 3PO; 4/hexanol method; 4/P; 5/Et; Biomaterials; Cellulose derivatives; Cellulose gels; Cellulose triphosphates; Chemical bonds; Fourier transform infrared spectroscopy; Gels; H; medical textile; Nuclear magnetic resonance spectroscopy; Phosphorylation; Raman scattering; Sterilizers; Synthesis (chemical); X ray diffraction analysis

Cellulose phosphates as biomaterials. II. Surface chemical modification of regenerated cellulose hydrogels - Granja, P.L.; Pouysgu, L.; Ptraud, M.; De Jso, B.; Baquey, C.; Barbosa, M.A. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 2001)
Cellulose regenerated by the viscose process was previously investigated as an implantable material in orthopedic surgery. It was envisaged to take advantage not only of its good matching with mechanical properties of bone but also of its hydroexpansivity, therefore allowing a satisfactory fixation to hard tissue. Both the osteoconduction and the lack of ostcoinduction of this material were demonstrated. Grafting of phosphate groups was then envisaged as the means to render cellulose more suitable for orthopedic applications by enhancing its bioactivity. In the present work, the previously optimized phosphorylation reaction was successfully adapted to the surface modification of regenerated cellulose. Modified materials were characterized by XPS, FTIR, and 31P MAS NMR spectroscopic studies, and contact angle measurements, revealing the chemical bond between phosphate groups and cellulose, as well as the hydrophilic nature of phosphorylated materials, which increases with increasing phosphate contents. Water swelling and resistance to gamma sterilization were assessed as well, showing that phosphorylated materials swell considerably in water and were not affected when sterilization was carried out under a nitrogen atmosphere. The increase in surface roughness attributed to chemical modification was demonstrated through laser rugosimetry measurements. © 2001 John Wiley & Sons, Inc. J. Appl. Polym. Sci.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JAPNAdoi: 10.1002/app.2194Language of Original Document: EnglishCorrespondence Address: Granja, P.L.; Laboratório de Biomaterials, Instituto de Engenharia Biomedica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: pgranja@ibmc.up.ptReferences: Williams, D.F., (1995) Med Der Technol, 6, p. 6;Gebelein, C.G., (1990) Biomimetic Polymers, , Plenum Press: New York; Hoffman, A.S., (1996) Biomaterials Science: An Introduction to Materials in Medicine, p. 124. , Ratner, B. D.; Hoffman, A. S.; Schoen, F. J.; Lemons, J. F., Eds.; Academic Press: San Diego, Chapter 2; Kasemo, B., Lausmaa, J., (1995) Environ Health Perspect, 102, p. 41; Ratner, B.D., (1980) J Biomed Mater Res, 14, p. 665; Poustis, J., Baquey, C., Chauveaux, D., (1994) Clin Mater, 16, p. 119; Gross, U., Müller-Mai, C., Voigt, C., (1992) Proceedings of the 4th World Biomaterials Congress, p. 192. , The Tissue Response on Cellulose Cylinders After Implantation in the Distal Femur of Rabbits, Berlin, Germany, April; Baquey, C., Barbié, C., More, N., Rouais, F., Poustis, J., Chauveaux, D., (1992) Proceedings of the 4th World Biomaterials Congress, p. 365. , In Vivo Study of the Bio-Stability of a Cellulose Material, Berlin, Germany, April; Chauveaux, D., Barbié, C., Barthe, X., Baquey, C., Poustis, J., (1990) Clin Mater, 5, p. 251; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D., Fr. Demande 8610331. 1986Eur. Pat. 0256906 A1, 1987U.S. Pat. 4,904,258, 1990Imbert, E., Letourneur, D., Jozefowicz, M., (1997) J Biomed Mater Res, 34, p. 417; Dowd, V., Yon, R.J., (1992) J Chromatogr, 627, p. 145; Kennedy, J.F., Cabral, J.M.S., (1983) Solid Phase Biochemistry: Analytical Synthetic Aspects, p. 253. , Scoutch, W. H., Ed. Wiley: New York, Chapter 7; Sugihara, J., Imamura, T., Yanase, T., (1982) J Chromatogr, 229, p. 193; Shih, T.Y., Martin, M.A., (1974) Biochemistry, 13, p. 3411; Holmquist, W.R., Schroeder, W.A., (1967) J Chromatogr, 26, p. 465; Thomaidis, T.S., Fidalgo, B.V., Harshman, S., Najjar, V.A., (1967) Biochemistry, 6, p. 3369; Granja, P.L., Pouységu, L., Pétraud, M., De Jéso, B., Baquey, C., Barbosa, M.A., (2001) J Appl Polym Sci, 82, p. 3341; Granja, P.L., Barbosa, M.A., Pouységu, L., De Jéso, B., Baquey, C., (1999) Frontiers in Biomedical Polymers Applications, 2, p. 195. , Ottenbrite, R., Ed. Technomic Press: Lancaster, PA; Granja, P.L., Baquey, C., Pouységu, L., Bareille, R., De Jéso, B., Barbosa, M.A., (1996) Polymers in Medicine and Surgery, PIMS'96, p. 73. , Glasgow, UK; Klemm, D., Philipp, B., Heinze, T., Heinze, U., Wagenknecht, W., (1998) Comprehensive Cellulose Chemistry: Fundamentals and Analytical Methods, 1, p. 9. , Wiley-VCH Verlag: Weinheim, Germany, Chapter 2; Zeronian, S.H., (1985) Cellulose Chemistry and Its Applications, p. 159. , Nevell, T.P. Zeronian, S.H., Eds. Ellis Horwood: Chichester, UK, Chapter 6; Granja, P.L., Pouységu, L., De Jéso, B., Rouais, F., Baquey, C., Barbosa, M.A., J Appl Polym Sci, , to appear; Ratner, B.D., Castner, D., (1997) Surface Analysis: The Principal Techniques, p. 43. , Vickerman, J.C., Ed. Wiley: Chichester, UK, Chapter 3; Dupraz, A., Nguyen, T.-P., Richard, M., Daculsi, G., Passuti, N., (1999) Biomaterials, 20, p. 663; Nguyen, T.-P., Dupraz, A., (1996) J Biomater Sci Polym Ed, 8, p. 141; Hanawa, T., Ota, M., (1991) Biomaterials, 12, p. 767; Morra, M., Volpe, C.D., (1998) J Biomed Mater Res, 42, p. 473; Garbassi, F., Morra, M., Occhiello, E., (1994) Polymer Surfaces: From Physics to Technology, p. 161. , Wiley: New York, Chapter 4; Vogler, E.A., (1993) Surfactant Science Series 49 (Wettability), p. 183. , Marcel Dekker: New York; Good, R.J., (1992) J Adhes Sci Technol, 6, p. 1269; Good, R.J., (1979) Surface and Colloid Science, 11, p. 1. , Good, R.J. Stromberg, R.R., Eds. Plenum Press: New York; Von Recum, A.F., Brown, C.E., Shannon, C.E., LaBerge, M., (1999) Handbook of Biomaterials Evaluation: Scientific, Technical, and Clinical Testing of Implant Materials, 2nd ed., p. 227. , von Recum, A.F., Ed. Edwards Brothers: Ann Arbor, MI, Chapter 13; Boyan, B.D., Batzer, R., Kieswetter, K., Liu, Y., Cochran, D.L., Szmuckler-Moncler, S., Dean, D.D., Schwartz, Z., (1998) J Biomed Mater Res, 39, p. 77; Richards, R.G., (1996) Injury, 27, pp. SC38; Brunette, D.M., (1988) Surface Characterization of Biomaterials, p. 203. , Ratner, B.D., Ed. Elsevier Science: Amsterdam; Kuptsov, A.H., Zhizhin, G.N., (1998) Handbook of Fourier Transform Raman and Infrared Spectra of Polymers, Physical Series Data, 45. , Elsevier: Amsterdam; Nyquist, R.A., Craver, C.D., (1977) The Coblentz Society Desk Book of Infrared Spectra, p. 399. , Craver, C.D., Ed. The Coblentz Society: French Village, MO; Nakamoto, K., (1977) Infrared and Raman Spectra of Inorganic and Coordination Compounds, 3rd ed., , Wiley-Interscience: New York; Klemm, D., Philipp, B., Heinze, T., Heinze, U., Wagenknecht, W., (1998) Comprehensive Cellulose Chemistry: Fundamentals and Analytical Methods, 1, p. 181. , Wiley-VCH Verlag: Weinheim, Germany, Chapter 3; Matthews, I.P., Gibson, C., Samuel, A.H., (1994) Clin Mater, 15, p. 191; Chamberlain, V.C., Lambert, B., Tang, F.-W., (1999) Handbook of Biomaterials Evaluation: Scientific, Technical, and Clinical Testing of Implant Materials, p. 253. , von Recum, A.F., Ed. Taylor & Francis: Philadelphia, Chapter 15; Phillips, G.O., Arthur J.C., Jr., (1985) Cellulose Chemistry and Its Applications, p. 290. , Nevell, T.P. Zeronian,S.H., Eds.; Ellis Horwood: Chichester, UK, Chapter 12; Ahmed, A.U., Rapson, W.H., (1972) J Polym Sci Part A Polym Chem, 10, p. 1945; Canet, D., (1996) Nuclear Magnetic Resonance: Concepts and Methods, , Wiley: Chichester, UK; Vogel, J., Russel, C., Gunther, G., Hartmann, P., Vizethum, F., Bergner, N., (1996) J Mater Sci Mater Med, 7, p. 495; Wu, Y., Glimcher, M.J., Rey, C., Ackerman, J.L., (1994) J Mol Biol, 244, p. 423; Rothwell, W.P., Waugh, J.S., Yesinowski, J.P., (1980) J Am Chem Soc, 102, p. 2637; Yokogawa, Y., Paz Reyes, J., Mucalo, M.R., Toriyama, M., Kawamoto, Y., Suzuki, T., Nishizawa, K., Kamayama, T., (1997) J Mater Sci Mater Med, 8, p. 407
Keywords: 2O; 3PO; 4/hexanol method; 4/P; 5/Et; Biomaterials; Cellulose derivatives; Cellulose phosphates; Chemical bonds; Chemical modification; Energy dispersive spectroscopy; Fourier transform infrared spectroscopy; H; Hydrogels; Phosphorylation; Regenerated cellulose hydrogels; Sterilization (cleaning); Surface modification; Surface roughness; X ray photoelectron spectroscopy

On combining classifiers using sum and product rules - Alexandre, L.A.; Campilho, A.C.; Kamel, M. (Pattern Recognition LettersPattern Recogn. Lett., 2001)
This paper presents a comparative study of the performance of arithmetic and geometric means as rules to combine multiple classifiers. For problems with two classes, we prove that these combination rules are equivalent when using two classifiers and the sum of the estimates of the a posteriori probabilities is equal to one. We also prove that the case of a two class problem and a combination of two classifiers is the only one where such equivalence occurs. We present experiments illustrating the equivalence of the rules under the above mentioned assumptions. © 2001 Elsevier Science B.V. All rights reserved.
Cited By (since 1996): 51Export Date: 21 November 2012Source: Scopusdoi: 10.1016/S0167-8655(01)00073-3Language of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; INEB-Inst. de Engenharia Biomedica, Rua Dr. Roberto Frias s/n, Porto 4200-465, Portugal; email: lfbaa@noe.ubi.ptReferences: Alexandre, L., Campilho, A., Kamel, M., Combining independent and unbiased classifiers using weighted average (2000) Proc. 15th Internat. Conf. on Pattern Recognition, 2. , IEEE Press, Barcelona, Spain;Bishop, C., (1995) Neural Networks for Pattern Recognition, , Oxford University Press, Oxford; Blake, C., Keogh, E., Merz, C., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Demuth, H., Beale, M., (1998) Neural Network Toolbox User's Guide, , The MathWorks, Inc; Hansen, L., Salamon, P., Neural network ensembles (1990) IEEE Trans. PAMI, 12 (10), pp. 993-1001; Hashem, S., Optimal linear combinations of neural networks (1997) Neural Networks, 10 (4), pp. 599-614; Kittler, J., Hatef, M., Duin, R., Combining classifiers (1996) Proc. Internat. Conf. on Pattern Recognition'96; Kittler, J., Hatef, M., Duin, R., Matas, J., On combining classifiers (1998) IEEE Trans. PAMI, 20 (3), pp. 226-239; Opitz, D., Maclin, R., Popular ensemble methods: An empirical study (1999) J. Artif. Intell. Res, 11, pp. 169-198; Richard, M., Lippmann, R., Neural network classifiers estimate Bayesian a posteriori probabilities (1991) Neural Comput, 3, pp. 461-483; Rogova, G., Combining the results of several neural network classifiers (1994) Neural Networks, 7 (5), pp. 777-781; Tax, D., Duin, R., Breukelen, M., Comparison between product and mean classifier combination rules (1997) Workshop on Statistical Techniques in Pattern Recognition, , Prague Czech Republic; Ueda, N., Optimal linear combination of neural networks for improving classification performance (2000) IEEE Trans. PAMI, 22 (2), pp. 207-215
Keywords: artificial neural network; Classification; Classifier fusion; Combinatorial mathematics; Combining classifiers; Equivalence classes; Estimation; K nearest-neighbours; Multiple classifiers; Neural networks; Pattern recognition; probability

Comparative effects of nacre water-soluble matrix and dexamethasone on the alkaline phosphatase activity of MRC-5 fibroblasts - Almeida, M.J.; Pereira, L.; Milet, C.; Haigle, J.; Barbosa, M.; Lopez, E. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2001)
In this study we demonstrate, for the first time, that dexamethasone and BMP-2 stimulated alkaline phosphatase (ALP) activity in MRC-5 fibroblasts, a cell line derived from human fetal lung. Previously we reported that the water-soluble matrix (WSM) of nacre obtained from the inner shell layer of the oyster Pinctada maxima, promoted an increase in ALP activity that was dose-dependent. In this work, we show that the effect of WSM is also time-dependent. As a comparison, the effect of WSM was also tested in bone marrow stromal cells because marrow and other bone surface-derived osteoblast stem cells have the inherent direct potential for osteogenesis. WSM promotes cell proliferation and ALP activity when tested with bone marrow cells in concentrations between 135 and 540 μg protein/mL. The effect of WSM on ALP activity of bone marrow stromal cells is similar to that obtained by dexamethasone. These results imply that MRC-5 fibroblasts respond to differentiating factors that promote osteoblastic phenotype in bone-derived cell cultures. © 2001 John Wiley & Sons, Inc.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/1097-4636(200111)57:2<306::AID-JBM1172>3.0.CO;2-HPubMed ID: 11484195Language of Original Document: EnglishCorrespondence Address: Lopez, E.; Lab. de Physiol. Gen. et Comparee, UMR CNRS 8572, Museum National d'Histoire Naturelle, 7 rue Cuvier, 75231 Paris Cedex 05, France; email: lopez@mnhn.frChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; BMP2 protein, human; Bmp2 protein, rat; bone morphogenetic protein 2; Bone Morphogenetic Proteins; Dexamethasone, 50-02-2; Glucocorticoids; Transforming Growth Factor betaReferences: Lopez, E., Vidal, B., Berland, S., Camprasse, S., Camprasse, G., Silve, C., Demonstration of the capacity of nacre to induce bone formation by human osteoblasts maintained in vitro (1992) Tissue Cell, 24, pp. 667-679;Lopez, E., Berland, S., Le Faou, A., Nacre, osteogenic and osteoinductive properties (1994) Bull Inst Océan Monaco, 14, pp. 49-57; Silve, C., Lopez, E., Vidal, B., Smith, D.C., Camprasse, S., Camprasse, G., Couly, G., Nacre initiates biomineralization by human osteoblasts maintained in vitro (1992) Calcif Tissue Int, 51, pp. 363-369; Atlan, G., Balmain, N., Berland, S., Vidal, B., Lopez, E., Reconstruction of human maxillary defects with nacre powder: Histological evidence for bone regeneration (1997) C R Acad Sci III, 320, pp. 253-258; Atlan, G., Delattre, O., Berland, S., Le Faou, A., Nabias, G., Cot, D., Lopez, E., Interface between bone and nacre implants in sheep (1999) Biomaterials, 20, pp. 1017-1022; Lamghari, M., Almeida, M.J., Berland, S., Huet, H., Laurent, A., Milet, C., Lopez, E., Stimulation of bone marrow cells and bone formation by nacre: In vivo and in vitro studies (1999) Bone, 25 S, pp. 91S-94S; Westbroek, P., Marin, F., A marriage of bone and nacre (1998) Nature, 392, pp. 861-862; Le Faou, A., Berland, S., Lallier, F., Lopez, E., Osteoinductive effects induced by nacre implanted in subcutaneous pouches in rat (1995) Calcif Tissue Int, 56 A, p. 156; Le Faou, A., Berland, S., Lallier, F., Lopez, E., Local regulation of the osteoinductive process induced by nacre in connective tissues (1996) Ann Endoc, 57 (SUPPL. 4A), p. 75; Aubin, J.E., Liu, F., Malaval, L., Gupta, A.K., Osteoblast and chondroblast differentiation (1995) Bone, (SUPPL. 2), pp. S77-S83; Huggins, C.B., Urist, M.R., Dentin matrix transformation: Rapid induction of alkaline phosphatase and cartilage (1970) Science, 167, pp. 896-897; Reddi, A.H., Huggins, C.B., Biochemical sequences in the transformation of normal fibroblasts in adolescent rats (1972) Proc Natl Acad Sci USA, 69, pp. 1601-1605; Glowacki, J., Mulliken, J.B., Demineralized bone implants (1985) Clin Plast Surg, 12 (2), pp. 233-241; Katagiri, T., Yamaguchi, A., Ikeda, T., Yoshiki, S., Wozney, J.M., Rosen, V., Wang, E.A., Suda, T., The nonosteogenic mouse pluripotent cell line, C3H10T1/2, is induced to differentiate into osteobtastic cells by recombinant human bone morphogenetic protein-2 (1990) Biochem Biophys Res Commun, 172, pp. 295-299; McCulloch, C.A.G., Tenenbaum, H.C., Dexamethasone induces proliferation and terminal differentiation of osteogenic cells in tissue culture (1986) Anat Rec, 215, pp. 397-402; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Bellows, C.G., Aubin, J.E., Determination of numbers of osteoprogenitors present in isolated fetal calvarial cells in vitro (1989) Dev Biol, 133, pp. 8-13; Bhargava, U., Bar-Lev, M., Bellows, C.G., Aubin, J.E., Ultrastructural analyses of bone nodules formed in vitro by isolated fetal rat calvaria cells (1988) Bone, 9, pp. 155-163; Wiren, K.M., Rodan, G.A., Dissociation between the effects of glucocorticosteroids on cell spreading and phenotypic expression (1985) The chemistry and biology of mineralized tissues, pp. 320-325. , Butler WT, editor. Birmingham, AL: EBSCO Media; Kasugai, S., Todescan, R., Nagata, T., Yao, K.-L., Butler, W.T., Sodek, J., Expression of bone matrix proteins associated with mineralized tissue formation by adult rat bone marrow cells in vitro: Inductive effects of dexamethasone on the osteoblastic phenotype (1991) J Cell Physiol, 147, pp. 111-120; Chen, T.L., Bates, R.L., Dudley, A., Hammonds, R.G., Amento, E.P., Bone morphogenetic protein-2b stimulation of growth and osteogenic phenotypes in rat osteobtast-like cells: Comparison with TGF-β1 (1991) J Bone Miner Res, 6, pp. 1387-1393; Hiraki, Y., Inoue, H., Shigeno, C., Sanma, Y., Bentz, H., Rosen, D.M., Asada, A., Suzuki, F., Bone morphogenetic proteins (BMP-2 and BMP-3) promote growth and expression of the differentiated phenotype of rabbit chondrocytes and osteoblastic MC3T3-E1 cells in vitro (1991) J Bone Miner Res, 6, pp. 1373-1385; Rosen, V., Thies, R.S., The BMP proteins in bone formation and repair (1992) Trends Genet, 8, pp. 97-102; Thies, R.S., Bauduy, M., Ashton, B.A., Kurtzberg, L., Wozney, J.M., Rosen, V., Recombinant human bone morphogenetic protein-2 induces osteoblastic differentiation in W-20-17 stromal cells (1992) Endocrinology, 130, pp. 1318-1324; Urist, M.R., Iwata, H., Ceccotti, P.L., Dorfman, R.L., Boyd, S.D., McDowell, R., Chien, C., Bone morphogenesis in implants of insoluble bone gelatin (1973) Proc Natl Acad Sci USA, 70, pp. 3511-3515; Almeida, M.J., Milet, C., Peduzzi, J., Pereira, L., Haigle, J., Barthélemy, M., Lopez, E., The effect of water-soluble matrix fraction extracted from the nacre of Pinctada maxima on the alkaline phosphatase activity of cultured fibroblasts (2000) J Exp Zool, 288, pp. 327-334; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Owen, M., Marrow stromal stem cells (1988) J Cell Sci, (SUPPL. 10), pp. 63-76; Triffitt, J.T., Initiation and enhancement of bone formation (1987) Acta Orthop Scand, 58, pp. 673-684; Triffitt, J.T., The stem cell of the osteoblast (1996) Principles of bone biology, pp. 39-50. , Bilezikian JP, Raisz LG, Rodan GA, editors. New York: Academic Press; Wharton, S.A., Hipkiss, A.R., Degradation of peptides and proteins of different sizes by homogenates of human MRC5 lung fibroblasts (1985) FEBS Lett, 184 (2), pp. 249-253; Harada, K., Oida, S., Sasaki, S., Chondrogenesis and osteogenesis of bone marrow-derived cells by bone-inductive factor (1988) Bone, 9, pp. 177-183; Tucker, R.F., Shipley, G.D., Moses, H.L., Growth inhibitor from BSC-1 cells closely related to platelet type β transforming factor (1984) Science, 226, pp. 705-707; Noda, M., Rodan, G.A., Type-β transforming growth factor inhibits proliferation and expression of alkaline phosphatase in murine osteoblast-like cells (1986) Biochem Biophys Res Commun, 140, pp. 56-65; Tintut, Y., Parhami, F., Boström, K., Jackson, S., Demer, L., cAMP stimulates osteoblast-like differentiation of calcifying vascular cells (1998) J Biol Chem, 273, pp. 7547-7553; Rickard, D.J., Sullivan, T.A., Shenker, B.J., Leboy, P.S., Kazhdan, I., Induction of rapid osteoblast differentiation in rat bone marrow stromal cell cultures by dexamethasone and BMP-2 (1994) Dev Biol, 161, pp. 218-228; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II. Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Green, S., Chambon, P., A superfamily of potentially oncogenic hormone receptors (1986) Nature, 324, pp. 615-617; Grigoriadis, A.E., Heersche, J.N.M., Aubin, J.E., Differentiation of muscle, fat, cartilage and bone from progenitor cells present in a bone-derived clonal cell population: Effect of dexamethasone (1988) J Cell Biol, 106, pp. 2139-2151; Leboy, P.S., Beresford, J.N., Devlin, C., Owen, M.E., Dexamethasone induction of osteoblast mRNAs in rat marrow stromal cell cultures (1991) J Cell Physiol, 146, pp. 370-378; Guerriero V., Jr., Florini, J.R., Dexamethasone effects on myoblast proliferation and differentiation (1980) Endocrinology, 106, pp. 1198-1202; Maor, G., Silbermann, M., Supraphysiological concentrations of dexamethasone induce elevation of calcium uptake and depression of [ 3H]-thymidine incorporation into DNA in cartilage in vitro (1986) Calcif Tissue Int, 39, pp. 284-290; Urist, M.R., Bone morphogenetic protein in biology and medicine (1996) Bone morphogenetic proteins: Biology, biochemistry and reconstructive surgery, pp. 7-27. , Lindholm TS, editor. Austin, TX: RG Landes Company; Wozney, J.M., Rosen, V., Byrne, T., Celeste, A.J., Moutsatsos, I., Wang, E.A., Growth factor influencing bone development (1990) J Cell Sci, 97 (SUPPL. 13), pp. 149-156; Takuwa, Y., Ohse, C., Wang, E.A., Wozney, J.M., Yamashita, K., Bone morphogenetic protein-2 stimulates alkaline phosphatase activity and collagen synthesis in cultured osteoblastic cells, MC3T3 (1991) Biochem Biophys Res Commun, 174, pp. 96-101; Jortikka, L., Target cells and receptors for bone morphogenetic protein (1996) Bone morphogenetic proteins: Biology, biochemistry and reconstructive surgery, pp. 65-73. , Lindholm TS, editor. Austin, TX: RG Landes Company; Canalis, E., Centrella, M., Urist, M.R., Effect of partially purified bone morphogenetic protein on DNA synthesis and cell replication in calvarial and fibroblast cultures (1985) Clin Orthop, 198, pp. 289-294; Centrella, M., Casinghino, S., Kim, J., Pham, T., Rosen, V., Wozney, J., McCarthy, T.L., Independent changes in type I and type II receptors for transforming growth factor β induced by bone morphogenetic protein 2 parallel expression of the osteoblast phenotype (1995) Mol Cell Biol, 15, pp. 3273-3281; Vukicevic, S., Luyten, F.P., Redi, A.H., Stimulation of the expression of osteogenic and chondrogenic phenotypes in vitro by osteogenin (1989) Proc Natl Acad Sci USA, 86, pp. 8793-8797
Keywords: alkaline phosphatase; Animals; article; Biomedical engineering; BMP-2; Bone; bone development; bone marrow; Bone Marrow Cells; Bone morphogenetic proteins; Cell culture; Cell Line; cell proliferation; Cells; concentration response; dexamethasone; differentiation inducing factor; dose response; Dose-Response Relationship, Drug; enzyme activity; fibroblast; Fibroblasts; Glucocorticoids; human; human cell; Humans; male; MRC-5 fibroblasts; Nacre; natural product; osteoblast; Ostreidae; oyster; phenotype; Proteins; Pulmonary diseases; Rats; Rats, Wistar; Solubility; stroma cell; time; Time Factors; Transforming Growth Factor beta; unclassified drug; Water; Water-soluble matrix

Corrosion behaviour of titanium in biofluids containing H 2O 2 studied by electrochemical impedance spectroscopy - Fonseca, C.; Barbosa, M.A. (Corrosion ScienceCorros Sci, 2001)
This work aims at studying the electrochemical behaviour of titanium in the presence of an artificial biofluid containing H 2O 2, mimicing the situation, where the metal is implanted in the human body and hydrogen peroxide is generated by an inflammatory reaction. A phosphate buffered saline (PBS) solution and two PBS/H 2O 2 solutions containing 50 and 150 mM of H 2O 2 were used to simulate the body fluids. The behaviour of the metal was monitored as a function of time by electrochemical impedance spectroscopy (EIS) for three weeks. After one week, the PBS/H 2O 2 solutions were replaced by fresh PBS solutions in order to simulate the end of the inflammatory process and recovery of the system. All the experiments were carried out at a constant temperature of 37 °C. From the simulation of the experimental EIS spectra, it was concluded that the corrosion resistance of titanium is strongly affected by the presence of H 2O 2 and when the peroxide is removed, the metal displays a sharp resistance increase. Furthermore, the oxides formed in H 2O 2 are rougher and display higher ionic conductivities than the oxides formed in the absence of peroxide. The study was complemented with potentiostatic experiments and scanning electron microscopy observation of the metal surfaces.
Cited By (since 1996): 73Export Date: 21 November 2012Source: ScopusCODEN: CRRSAdoi: 10.1016/S0010-938X(00)00107-4Language of Original Document: EnglishCorrespondence Address: Fonseca, C.; Inst de Engenharia Biomedica, Porto, PortugalReferences: Hugot-Le-Goff, A., (1986) Thin Solid Films, 142, p. 193;Pascal, P., (1963) Nouveau Traité de Chimie Minérale, 14. , Masson & Cie, Paris; Laing, P.G., Ferguson, A.B., Hodge, E.S., (1967) J. Biomed. Mater. Res., 1, p. 135; Dorr, L.D., Bloebaum, R., Emmanual, J., Meldrum, R., (1990) Clin. Orthop., 261, p. 82; Meachim, G., Williams, D.F., (1973) J. Biomed. Mat. Res., 7, p. 555; Sundgren, J.E., Bodö, P., Lundström, I., (1986) J. Colloid Interf. Sci., 10, p. 9; McQueen, D., Sundgren, J.E., Ivarsson, B., Lundström, I., Ekenstam, B., Svensson, A., Brånemark, P.I., Albrektsson, T., Auger electron spectroscopic studies of titanium implants (1982) Clinical Applications of Biomaterials, p. 179. , A.J.C. Lee, T. Albrektsson, P.I. Brånemark (Eds.), Wiley; Tengvall, P., Elwing, H., Sjöqvist, L., Lundström, I., Bjursten, L.M., (1989) Biomaterials, 10, p. 118; Tengvall, P., Lundström, I., (1992) Clinical Mater., 9, p. 115; Tengvall, P., Elwing, H., Lundström, I., (1989) J. Colloid Interf. Sci., 130, p. 405; Sun, Z.L., Wataha, J.C., Hanks, C.T., (1997) J. Biomed. Mater. Res., 34, p. 29; Schepers, E., Clercq, M., Ducheyne, P., Tissue response to a bioactive glass-metal interface (1987) Implant Materials in Biofunction, p. 79. , C.D. Putter (Ed.), Elsevier, Amsterdam; Wang, J.Y., Tsukayama, D.T., Wicklund, B.H., Gustilo, R.B., (1996) J. Biomed. Mater. Res, 32, p. 655; Mu, Y., Kobayashi, T., Sumita, M., Yamamoto, A., Hanawa, T., (2000) J. Biomed. Mat. Res., 49, p. 238; Boukamp, B., (1989) Equivalent Circuit, User's Manual, 2nd Revised Edition, , Un. Twente Enschede, The Netherlands; MacDonald, J.R., Johnson, W.B., (1987) Impedance Spectroscopy, pp. 154-156. , John Wiley, New York; MacDonald, D.D., Urquidi-MacDonald, M., (1985) J. Electrochem. Soc., 133, p. 2018; Pan, J., Thierry, D., Leygraf, C., (1994) J. Biomed. Mater. Res., 28, p. 113; Chao, C.Y., Lin, L.F., MacDonald, D.D., (1982) J. Electrochem. Soc., 129, p. 1874; Armstrong, R.D., Edmondson, K., (1973) Electrochim. Acta, 18, p. 937; Pan, J., Thierry, D., Leygraf, C., (1996) Electrochim. Acta, 41, p. 1143; Cole, K.S., Cole, R.H., (1941) J. Chem. Phys., 9, p. 341; Rammlet, U., Reinhard, G., (1987) Corros. Sci., 27, p. 373; Mansfeld, F., Shih, H., Greene, H., Tsai, C.H., Analysis of EIS-data for common corrosion processes (1991) Int. Symp. on Electrochem. Imp. Analysis and Interpretation, , ASTM STP, San Diego; Park, J.R., MacDonald, D.D., (1983) Corros. Sci., 23, p. 295; Kader, J.M.E., Din, A.M.E., (1979) Br. Corros. J., 14, p. 40; Kader, J.M.E., Wahab, F.M.E., Shayeb, H.A.E., Khedr, M.G., (1981) Br. Corros. J., 16, p. 111; Hanawa, T., Ota, M., (1991) Biomaterials, 12, p. 767; Pan, J., Thierry, D., Leygraf, C., (1996) J. Biomed. Mater. Res., 30, p. 393; Hanawa, T., Ota, M., (1992) Appl. Surf. Sci., 55, p. 269; Le Mehaute, A., (1984) J. Stat. Phys., 36, p. 665; De Levie, Electrochemical response of porous and rough electrodes Advances in Electrochemistry and Electrochemical Engineering, 6. , P. Delahay (Ed.), Interscience, NY
Keywords: Biomaterials; Body fluids; Corrosion resistance; Electrochemical corrosion; electrochemical process; hydrogen peroxide; impedance technique; Implants (surgical); Phosphate buffered saline; Solutions; Spectroscopy; Titanium

Effect of chemical composition on hydrophobicity and zeta potential of plasma sprayed HA/CaO-P 2O 5 glass coatings - Ferraz, M.P.; Monteiro, F.J.; Serro, A.P.; Saramago, B.; Gibson, I.R.; Santos, J.D. (BiomaterialsBiomaterials, 2001)
Multilayered plasma sprayed coatings on the surface of Ti-6Al-4V alloys have been prepared, which were composed of an underlayer of HA and a surface layer of a CaO-P 2O 5 glass-HA composite, with 2 or 4 wt% of glass. Contact angle and surface tension variation with time, for both water and a protein solution, were determined by the sessile and pendent drop methods respectively using the ADSA-P software. Wettability studies showed that hydrophobicity of the coatings increase with the glass addition. The work of adhesion of albumin was also altered in a controlled manner by the addition of the CaO-P 2O 5 glass, being lower on the composite coatings than on HA. Zeta potential (ZP) results showed that composite coatings presented a higher net negative charge than HA coatings and that ZP values were also influenced by the content of the glass. This study demonstrated that the surface properties of those coatings may be modified by the addition of CaO-P 2O 5 glass. © 2001 Published by Elsevier Science Ltd.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00059-XPubMed ID: 11603581Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Inst. de Engenharia Biomedica (INEB), Rua do Campo Alegre 823, 4150 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Calcium Compounds; Durapatite, 1306-06-5; lime, 1305-78-8; Oxides; Phosphorus Compounds; phosphorus pentoxide, 1314-56-3; Serum Albumin, BovineReferences: Klein, C.P.A.T., Patka, P., Van der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalciumphosphate, hydroxyl-apatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65;Jansen, J.A., Van der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 14, pp. 603-610; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci: Mater Med, 5, pp. 11-17; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci: Mater Med, 7, pp. 21-28; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., Adhesion and microstructural characterisation of plasma-sprayed hydroxyapatite/glass ceramic coatings onto Ti-6Al-4V substrates (1998) Surf Coating Technol, 102, pp. 191-196; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced HA plasma-sprayed coatings (1999) J Mater Sci: Mater Med, 10 (9), pp. 567-576; Lapin, M., Warocquier-Clérout, R., Legris, C., Degrange, M., Luizard, M.F.S., Correlation between roughness and wettability, cell adhesion and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Williams, D.F., (1982) Fundamental aspects of biocompatibility, , Boca Raton: CRC Press; Adamson, W., (1990) Physical chemistry of surfaces, 5th ed., , New York: Wiley; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites (1995) J Mater Sci: Mater Med, 6, pp. 348-352; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Chen, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation of axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Coll and Surf, 43, pp. 151-197; Cheng, P., Neumann, A.W., Computational evaluation of axisymmetric drop shape analysis-profile (ASA-P) (1992) Coll and Surf, 62, pp. 297-306; Young, T., (1835) Miscellaneous works, 1, p. 418. , Peacock G, editor. London: Murray; Schrader, M.E., Young Dupré revisited (1995) Langmuir, 11, p. 3585; Owens, D.K., Wendt, R.D., Estimation of the surface free energy of polymers (1969) J Appl Polym Sci, 13, pp. 1741-1769; Williams, R.L., Williams, D.F., Albumin adsorption on metal surfaces (1988) Biomaterials, 9, pp. 206-212; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Tripp, B.C., Magda, J.J., Andrade, J.D., Adsorption of globular proteins at the air/water interface as measured via dynamic surface tension: Concentration dependence, mass-transfer and adsorption kinetics (1995) J Coll Interface Sci, 173, pp. 16-27; Voigt, A., Thiel, O., Williams, D., Policova, Z., Zing, W., Neumann, A.W., Axisymmetric drop shape analysis (ADSA) applied to protein solutions (1991) Coll and Surf, 58, pp. 315-326; Suzuki, T., Nishizawa, K., Yokogawa, Y., Kameyama, T., Time-dependent variation of the surface structure of bioceramics in tissue culture medium and the effect of adhesiveness of cells (1996) J Ferment Bioeng, 81, pp. 226-232; Susuki, T., Yamamoto, T., Yoriyama, M., Kameyama, T., Surface instability of calcium phosphate ceramics in tissue culture medium and the effect on adhesion and growth of anchorage-dependent animal cells (1997) J Biomed Mater Res, 34, pp. 504-517; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Coll and Surf B: Biointerfaces, 2, pp. 517-566; Kondori, K., Soito, M., Takebe, T., Yasukawa, A., Adsorption of bovine serum albumin on synthetic carbonate calcium hydroxyapatite (1995) J Coll Interface Sci, 184, pp. 124-129
Keywords: Adhesion; alloy; analytic method; article; bovine serum albumin; Calcium Compounds; calcium oxide; chemical composition; Chemical modification; Coatings; Composition; computer program; Contact angle; Durapatite; glass; hydrophobicity; hydroxyapatite; Hydroxyapatite glass composites; oxide; Oxides; pentoxide; Phosphorus Compounds; priority journal; protein; Serum Albumin, Bovine; Sprayed coatings; Surface charge; Surface Properties; Surface tension; Surface tension zeta potential; time; unclassified drug; Water; wettability; Wetting; X-Ray Diffraction; Zeta potential

HA and double-layer HA-P 2O 5/CaO glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behavior - Ferraz, M.P.; Fernandes, M.H.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2001)
Human osteoblastic bone marrow derived cells were cultured for 28 days onto the surface of a glass reinforced hydroxyapatite (HA) composite and a commercial type HA plasma sprayed coatings, both in the "as-received" condition and after an immersion treatment with culture medium during 21 days. Cell proliferation and differentiation were analyzed as a function of the chemical composition of the coatings and the immersion treatment. Cell attachment, growth and differentiation of osteoblastic bone marrow cells seeded onto "as-received" plasma sprayed coatings were strongly affected by the time-dependent variation of the surface structure occurring during the first hours of culture. Initial interactions leading to higher amounts of adsorbed protein and zeta potential shifts towards negative charges appeared to result in surface structures with better biological performance. Cultures grown onto the pretreated coatings showed higher rate of cell proliferation and increased functional activity, as compared to those grown onto the corresponding "as-received" materials. However, the cell behavior was similar in the glass composite and HA coatings. The results showed that the glass composites present better characteristics for bone cell growth and function than HA. In addition, this work also provide evidence that the biological performance of the glass composites can be modulated and improved by manipulations in the chemical composition, namely in the content of glass added to HA. © 2001 Kluwer Academic Publishers.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1011245828046Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Rua Dr. Manuel Pereira da Silva, 4200 Porto, PortugalReferences: Klein, C.P.A.T., Patka, P., Van der Lubbe, H.B.M., (1991) J. Biomed. Mater. Res., 25, p. 53;Jansen, J.A., Van Der Waerden, J.P.C.M., Wolke, J.G.C., (1993) J. Mater. Sci Mater. Med., 4, p. 466; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., (1994) J. Mater. Sci. Mater. Med., 5, p. 11; Courteney-Harris, R.G., Kayser, M.V., Downes, S., (1995) Biomaterials, 16, p. 489; Labat, B., Chanson, A., Frey, J., (1995) J. Biomed. Mater. Res., 29, p. 1397; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci. Mater. Med., 7, p. 21; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., (1999) J. Mater. Sci: Mater. Med., 10, p. 567; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mat. Res., 45, p. 376; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 47, p. 603; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., (1997) J. Biomed. Mat. Res., 34, p. 247; Ong, J.L., Prince, C.W., Lucas, L.C., (1995) J. Biomed. Mat. Res., 29, p. 165; Gregoire, M., Orly, I., Kerebel, L.-M., Kerebel, B., (1987) Biol. Cell., 255, p. 59; Morgan, J., Holtman, K., Stanford, C., (1995) J. Dent. Res., 74, p. 190; Chou, L., Firth, J.D., Uitto, V.-J., Brunette, D.M., (1995) J. Cell. Sci., 108, p. 1563; Chou, L., Marek, B., Wagner, W.R., (1999) Biomaterials, 20, p. 977; Susuki, T., Nishizawa, K., Yokogawa, Y., Nagata, F., Kawamoto, Y., Kameyama, T., (1996) J. Ferment. Bioeng., 81, p. 226; Lampin, M., Warocquier-Clerout, R., Legris, C., Degrange, M., Sigot-Luizard, M.F., (1997) J. Biomed. Mater. Res., 36, p. 99; Best, S., Sim, B., Kayser, M., Downes, S., (1997) J. Mater. Sci. Mater. Med., 8; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., (1999) J. Mater. Sci. Mater. Med., 10, p. 663; Maniatopoulos, C., Sodek, J., Melcher, A., (1988) Cell Tissue Res., 254, p. 317; Gundle, R., Joyner, C.Y., Triffit, J.T., (1995) Bone, 16, p. 597; Fernandes, M.H., Costa, M.A., Carvalho, G.S., (1997) J. Mater. Sci. Mater. Med., 8, p. 61; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1997) J. Mater. Sci. Mater. Med., 8, p. 233; Fernandes, M.H., (1999) J. Biomat. App., 14, p. 113; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., (1993) Handbook of Experimental Pharmacology, p. 149. , edited by J. R. Mundy and T. J. Martin (Springer-Verlag, Berlin); Stein, G.S., Lian, J.B., (1993) Cellular and Molecular Biology of Bone, p. 47. , edited by M. Noda (Academic Press Inc., Tokyo); Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Biomaterials, , in press; Coelho, M.J., Fernandes, M.H., Biomaterials, , in press; Anderson, H.C., Morris, D.C., (1993) Handbook of Experimental Pharmacology, p. 267. , edited by J. R. Mundy and T. J. Martin (Springer-Verlag, Berlin); Krajewski, A., Piancastelli, A., Malavolti, R., (1998) Biomaterials, 19, p. 637; Krajewski, A., Malavolti, R., Piancastelli, A., (1996) Biomaterials, 17, p. 53; Ducheyne, P., Kim, C.S., Pollack, S.R., (1992) J. Biomed. Mater. Res., 26, p. 147; Susuki, T., Yamamoto, T., Toriyama, M., Nishizawa, K., Yokogawa, Y., Mucalo, M.R., Kawamoto, Y., Kameyama, T., (1997) J. Biomed. Mater. Res., 34, p. 507; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Biomaterials, , in press; Kokubo, T., (1993) Bone-Bonding Biomaterals, p. 31. , edited by P. Ducheyne, T. Kokubo and C. A. Blitterswijk (Reed Health-Care Communications, Leiden, The Netherlands); Daculsi, G., Legeros, R.Z., Henghebaert, M., Barbieux, I., (1990) Calcif. Tissue Int., 46, pp. 20-27; Bagambisa, F.B., Joos, U., Schilli, W., (1993) J. Biomed. Mat. Res., 27, pp. 1047-1055; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., (1995) J. Biomed. Mat. Res., 29, pp. 89-99; Gwynn, I.A.P., (1994) J. Mater. Sci. Mater Med., 5, pp. 357-360; Ghannam, E.L., Ducheyne, P., Spapiro, I., (1995) J. Biomed Mat. Res., 29, pp. 359-370; Kirkpatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., (1997) J. Mater. Sci. Mater Med., 8, pp. 131-141; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., J. Biomed. Mater. Res., , in press
Keywords: Adsorption; alkaline phosphatase; article; Biomedical engineering; Bone; bone marrow; bone marrow cell; Calcium; calcium oxide; cell adhesion; Cell culture; cell differentiation; cell growth; cell proliferation; chemical composition; Coatings; controlled study; culture medium; enzyme activity; glass; Growth kinetics; human; human cell; hydroxyapatite; immersion; osteoblast; oxygen; performance; phosphorus; priority journal; protein binding; protein content; Proteins; Scanning electron microscopy; Surface charge; surface property; time; X ray diffraction

Histological studies of double layer HA/CaO-P 2O 5 glass plasma sprayed coatings using Rabbit model - Ferraz, M.P.; Santos, J.D.; Afonso, A.; Vasconcelos, M.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2001)
The in vivo biological performance of a double layer HA/CaO-P 2O 5 glass and HA plasma sprayed coatings was assessed, using cylindrical implants that were placed in rabbits tibiae and histologically characterised after 2, 4, 8 and 16 weeks of implantation. For both types of coatings, long-term histological results indicated successful contact between implanted materials and bone, with organised new bone established at the interface. The main difference between the two coatings corresponded to the shorter implantation periods, where the composite coating induced faster osteointegration than HA coating. The faster formation of organised bone for composite coatings is discussed in terms of the presence of phase composition in the coatings structure.
Conference code: 57760Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; Instituto de Engenharia Biomedica, (INEB), Porto, PortugalReferences: Lacefield, W.R., (1988) Bioceramics: Material Characteristics Versus In Vivo Behaviour, pp. 72-80. , P. Ducheyne, J.E. Lemons. New York: New York Academy of Science Publishers;Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) J Biomed Mater Res, 28, pp. 961-967; Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) J Biomed Mater Res, 28, pp. 909-917; Burnie, J., Gilchrist, T., (1983) Ceramic in Surgery, pp. 169-176. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Ferraz, M.P., Fernandes, M.H., Trigo Cabrai, A., Santos, J.D., Monteiro, F.J., (1999) J Mater Sci Mater Med, 10 (9), pp. 567-576; Oonishi, H., Hench, L.L., Wilson, J., Sugihara, F., Tsuji, E., Kushitani, S., Iwak, H., (1999) J Biomed Mater Res, 44, pp. 31-43; Kitsugi, T., Nakamura, T., Oka, M., Senaha, Y., Got, T., (1996) J Biomed Mater Res, 30, pp. 261-269; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Wolke, J.G.V., De Groot, K., (1991) J Biomed Mater Res, 25, pp. 53-65
Keywords: Bond strength (materials); Bone; Double layer coatings; hydroxyapatite; Implants (surgical); In vivo evaluation; Interfaces (materials); morphology; Phase composition; Phosphates; Plasma sprayed coatings; Rabbit model; Scanning electron microscopy; Sprayed coatings; X ray diffraction analysis

Microstructural characterization and in vitro apatite formation in CaO-P 2O 5-TiO 2-MgO-Na 2O glass-ceramics - Zhang, Y.; Santos, J.D. (Journal of the European Ceramic SocietyJ Eur Ceram Soc, 2001)
Bulk calcium phosphate glass and glass-ceramic with CaO/P 2O 5 molar ratio = 1.25 were prepared through introducing small amounts of Na 2O, MgO, and TiO 2 into the glass. Using XRD analysis, biocompatible β-Ca 2P 2O 7 (β-DCP) and more soluble Ca and Na-containing phases were clearly identified in the microstructure. In vitro bioactivity was assessed by immersion testing in SBF-simulated body fluid and apatite crystals were formed after 4 and 8 weeks of soaking. Porous microstructure was produced through dissolution of soluble phases and desirable porous structure may be achieved by controlling size and distribution of these phases and the leaching process. Therefore, this glass-ceramic is expected to be used as bone repair and regeneration implants and drug delivery carrier.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: JECSEdoi: 10.1016/S0955-2219(00)00202-8Language of Original Document: EnglishCorrespondence Address: Zhang, Yong; Inst de Engenharia Biomedica, Porto, PortugalReferences: Hench, L.L., Bioceramics: From concept to clinic (1991) J. Am. Ceram. Soc., 74, pp. 1487-1510;Hench, L.L., Anderson, Ö., (1993) An Introduction to Bioceramics, p. 41. , ed. L. L. Hench and J. Wilson. World Scientific, Singapore; Nakamura, T., Yamamuro, T., Higashi, S., Kokubo, T., Ito, S., A new glass-ceramic for bone replacement: Evaluation of its bonding to bone tissue (1985) J. Biomed. Mater. Res., 19, pp. 685-698; Höland, W., Vogel, W., Nauman, K., Gummel, J., Interface reactions between machinable bioactive glass-ceramics and bone (1985) J. Biomed. Mater. Res., 19, pp. 305-312; Abe, Y., Naruse, A., Hosoe, M., Fukui, H., Hasegawa, J., Development of calcium phosphate glass-ceramics for biomaterials (1975) The 1975 Symposium on Biomaterials, pp. 202-207. , Kyoto; Abe, Y., Calcium phosphate glass-ceramics for biomedical application. . .especially on microporous glass-ceramics (1990) Inter. Forum on Fine Ceramics '90, pp. 78-82. , Nagoya; Kasuga, T., Abe, Y., Novel calcium phosphate ceramics prepared by powder sintering and crystallization of glasses in the pyrophosphate region (1998) J. Mater. Res., 13, pp. 1-4; Kasuga, T., Abe, Y., Calcium phosphate invert glasses with soda and titania (1999) J. Non-Cryst. Solids, 243, pp. 70-74; Hench, L.L., Bioactive ceramics (1988) Bioceramics: Materials Characteristics Versus in Vivo Behavior, pp. 54-71. , ed. P. Ducheyne and J. Lemons. Annals of New York Academy of Sciences, New York; Kokubo, T., Ito, S., Sakka, S., Yamamuro, T., Formation of a high-strength bioactive glass-ceramic in the system MgO-CaO-SiO 2-P 2O 5 (1986) J. Mater. Sci., 21, pp. 536-540; Ohtsuki, C., Kushitani, H., Kokubo, T., Kotani, S., Yamamuro, T., Apatite formation on the surface of Ceravital-type glass-ceramic in the body (1991) J. Biomed. Mater. Res., 25, pp. 1363-1370; Ohtsuki, C., Kokubo, T., Yamamuro, T., Compositional dependence of bioactivity of glasses in the system CaO-SiO 2- Al 2O 3: Its in vitro evaluation (1992) J. Mater. Sci: Mater. in Med., 3, pp. 119-125; Ohtsuki, C., Kokubo, T., Yamamuro, T., Mechanism of apatite formation on CaO-SiO 2-P 2O 5 glasses in a simulated body fluid (1992) J. Non-Cryst. Solids, 143, pp. 84-89; Hosono, H., Zhang, Z., Abe, Y., Porous glass-ceramic in the CaO-TiO 2-P 2O 5 system (1989) J. Am. Ceram. Soc., 72, pp. 1587-1590; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strength bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 331-343; Kokubo, T., Kushitani, H., Kitsugi, T., Yamamuro, T., Solution able to reproduce in vivo surface-structure changes of bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 721-734; Rey, C., Frèche, M., Heughebaert, M., Heughebaert, J.C., Lacout, J.L., Lebugle, A., Szilagyi, J., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behavior (1991) Bioceramics, 4, pp. 57-64. , ed. W. Bonfield, G. W. Hastings and K. E. Tanner. Butterworth-Heinemann, London; Vogel, J., Schulze, K.-J., Reif, D., Hartmann, P., Platzbecker, U., Leuner, B., Resorbable porous phosphate invert glasses-first in vitro and in vivo results (1997) Bioceramics, 10, pp. 57-60. , ed. L. Sedel and C. Rey. Elsevier Science; Ohtsuki, C., Kokubo, T., Neo, M., Kotani, S., Yamamuro, T., Nakamura, T., Bando, Y., Bone-bonding mechanism of sintered β-3CaO·P 2O 5 (1991) Phosphorus Res. Bulletin, 1, pp. 191-196; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J. Biomed. Mater. Res., 27, pp. 999-1006; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Yamamuro, T., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J. Mater. Sci.: Mater. in Med., 3, pp. 79-83; Blumenthal, N.C., Mechanism of inhibition of calcification (1989) Clin. Orthop. Rel. Res., 247, pp. 279-289
Keywords: Apatite; Bioactivity; Calcium phosphate glass; Ceramic materials; Crystal microstructure; Crystallization; dissociation; glass; Glass ceramics; Leaching; Lime; Magnesia; Phosphorus Compounds; Porous materials; Sodium compounds; Solubility; Titanium dioxide

Mineralization of regenerated cellulose hydrogels - Granja, P.L.; Ribeiro, C.C.; De Jéso, B.; Baquey, C.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2001)
Due to their high water swelling, regenerated cellulose hydrogels and sponges were pre-incubated in a Ca-containing solution, and their mineralization was investigated. Results obtained demonstrate that a simple pre-incubation treatment in a Ca containing solution can induce mineralization in materials with limited or no tendency to mineralize. The minerals formed had an apatitic carbonated and poorly crystalline structure, resembling carbonated hydroxyapatite found in bone mineral. The apatitic layer formed showed a relatively accelerated growth using this technique, exhibiting nodules in their macroscopic structure, which seem to indicate lateral growth. The porous structure of regenerated cellulose sponges was also homogeneously mineralized using this technique. © 2001 Kluwer Academic Publishers.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1013960601330Language of Original Document: EnglishCorrespondence Address: Granja, P.L.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Portugal and Universidade do Porto, Rua do Campo Alegre, 823-4150-180 Porto, Portugal; email: pgranja@ibmc.up.ptTradenames: Cellspon, Hexabio, France; Regenerated cellulose hydrogel (CRV), Hexabio, FranceManufacturers: Cellomeda, Finland; Hexabio, FranceReferences: Abdel-Fattah, W.I., El-Sayed, A.M., Ali, F.M., Beheri, H.H., (1994) Biomaterials, 15, p. 643;Schwartz, Z., Braun, G., Kohavi, D., Brooks, B., Amir, D., Sela, J., Boyan, B., (1993) J. Biomed. Mater. Res., 27, p. 1029; Royer, P., Amrah-Bouali, S., Freche, M., Rey, C., Rouquet, N., Bonel, G., (1992) Bioceramics, 5, p. 95. , edited by T. Yamamuro, T. Kokubo and T. Nakamura (Kobunshi-Kankokai, Kyoto, Japan); Krajewski, A., Ravaglioli, A., Mongiorgi, R., Moroni, A., (1988) J. Biomed. Mater. Res., 22, p. 445; Hench, L.L., (1998) J. Biomed. Mater. Res., 41, p. 511; Hayakawa, S., Tsuru, K., Iida, H., Ohtsuki, C., Osaka, A., (1996) J. Ceram. Soc. Jpn., 104, p. 1000; Kitsugi, T., Yamamuro, T., Nakamura, T., Kokubo, T., (1989) J. Biomed. Mater. Res., 23, p. 631; Li, P., Ye, X., Kangasniemi, I., De Blieck-Hogervorst, J.M.A., Klein, C.P.A.T., De Groot, K., (1995) J. Biomed. Mater. Res., 29, p. 325; Li, P., Ohtsuki, T., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., (1993) J. Mater. Sci.: Mater. Med., 4, p. 127; Damen, J.J.M., Ten Cate, J.M., (1989) J. Dent. Res., 68, p. 1355; Leitão, E., Barbosa, M.A., De Grout, K., (1995) J. Mater. Sci.: Mater. Med., 6, p. 849; Li, P., Kangasniemi, I., De Grout, K., (1994) J. Am. Ceram. Soc., 77, p. 1307; Lowenberg, B., Chernecky, R., Shiga, A., Davies, J.E., (1991) Cells & Materials, 1, p. 177; Hanawa, T., Ota, M., (1991) Biomaterials, 12, p. 767; Damen, J.J.M., Ten Cate, J.M., Ellingsen, J.E., (1991) J. Dent. Res., 7, p. 1346; Radder, A.M., Van Loon, J.A., Puppels, G.J., Van Blitterswijk, C.A., (1995) J. Mater. Sci.: Mater. Med., 6, p. 510; Gaillard, M.L., Van Blitterswijk, C.A., (1994) J. Mater. Sci.: Mater. Med., 5, p. 695; Golomb, G., (1992) J. Mater. Sci.: Mater. Med., 3, p. 272; Golomb, G., Wagner, D., (1991) Biomaterials, 12, p. 397; Verheyen, C.C.P.M., De Wijn, J.R., Van Blitterswijk, C.A., De Grout, K., Rozing, P.M., (1993) J. Biomed. Mater. Res., 27, p. 433; Stupp, S.I., Ciegler, G.W., (1992) J. Biomed. Mater. Res., 26, p. 169; Bonfield, W., (1988) Bioceramics: Materials Characteristics vs In Vivo Behavior, p. 173. , edited by P. Ducheyne and J. E. Lemons (Ann. New York Academy of Sciences., NY, USA); Suzuki, K., Kobayashi, R., Yokoyama, Y., Harada, Y., Kokubo, T., (1993) Bioceramics, 6, p. 245. , edited by P. Ducheyne and D. Christiansen (Butterworth-Heinemann, Guilford, UK); Tanahashi, M., Hata, K., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1992) Bioceramics, 5, p. 57. , edited by T. Yamamuro, T. Kokubo and T. Nakamura (Kobunshi-Kankokai, Kyoto, Japan); Kokubo, T., Hata, K., Nakamura, T., Yamamuro, T., (1991) Bioceramics, 4, p. 113. , edited by W. Bonfield, G. W. Hastings and K. E. Turner (Butterworth-Heinemann, Guildford, UK); Oyane, A., Minoda, M., Miyamoto, T., Takahashi, R., Nakanishi, K., Kim, H.M., Kokubo, T., Nakamura, T., (1999) J. Biomed. Mater. Res., 47, p. 367; Osaka, A., Ohtsuki, C., Tsuru, K., (1995) Bioceramics, 8, p. 441. , edited by J. Wilson, L. L. Hench and D. Greenspon (Pergamon Press, New York, USA); Li, S., Liu, Q., De Wijn, J., De Grout, K., Zhou, B., (1996) J. Mater. Sci. Lett., 15, p. 1882; Hossainy, S.F.A., Hubbell, J.A., (1994) Biomaterials, 15, p. 921; Granja, P.L., Barbosa, M.A., Pouységu, L., De Jésu, B., Baquey, C., (1999) Frontiers in Biomedical Polymers Applications 2, p. 195. , edited by R. Ottenbrite (Technomic Press, Lancaster, PA, USA); Granja, P.L., Pouységu, L., De Jésu, B., Rouais, F., Baquey, C., Barbosa, M.A., (2001) J. Mater. Sci.: Mater. Med., , In press; Tanahashi, M., Matsuda, T., (1997) J. Biomed. Mater. Res., 34, p. 305; Li, S., Liu, Q., De Wijn, J., Wolke, J., Zhou, B., De Grout, K., (1997) J. Mater. Sci.: Mater. Med., 8, p. 543; Kato, E., Eika, Y., Ikada, Y., (1996) J. Biomed. Mater. Res., 32, p. 687; Mucalo, M.R., Yokogawa, Y., Toryiama, M., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, N., (1995) J. Mater. Sci.: Mater. Med., 6, p. 597; Mucalo, M.R., Yokogawa, Y., Suzuki, T., Kawamoto, Y., Nagata, K., Nishizawa, F., (1995) J. Mater. Sci.: Mater. Med., 6, p. 658; Poustis, J., Baquey, C., Chauveaux, D., (1994) Clin. Mater., 16, p. 119; Chauveaux, D., Barbié, C., Barthe, X., Baquey, C., Poustis, J., (1990) Clin. Mater., 5, p. 251; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D., (1986), Fr. Patent No. 8610331Eur. Patent No. 0256906 A1 (1987)US Patent No. 4904258 (1990)Martson, M., Viljanto, J., Hurme, T., Laippala, P., Saukko, P., (1999) Biomaterials, 20, p. 1899; Pajulo, O., Lonnberg, B., Lonnqvist, K., Viljanto, J., (1993) Abstracts Books of the XXXVIII Congress of The European Society for Surgical Research ESSR, p. 156. , edited by H. Aro and J. Niinikovski (Turku, Finland); Kokubo, T., (1990) Handbook of Bioactive Ceramics: Bioactive Glasses and Glass-Ceramics, 1, p. 41. , edited by T. Yamamuro, L. L. Hench and J. Wilson (CRC Press, Boca Raton, FL, USA); Ribeiro, C.C., (1994), MSc Thesis. Porto, Portugal, Faculdade de Engenharia da Universidade do PortoRhee, S.-H., Tanaka, J., (1999) Biomaterials, 20, p. 2155; Miyaji, F., Kim, H.-M., Handa, S., Kokubo, T., Nakamura, T., (1999) Biomaterials, 20, p. 913; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 35; Sauer, G.R., Wuthier, R.E., (1988) J. Biol. Chem., 263, p. 13718; Elliot, J.C., (1994) "Structure and Chemistry of the Apatites and Other Calcium Orthophosphates", Studies in Inorganic Chemistry Series 18, , Elsevier, Amsterdam, The Netherlands; Hanawa, T., Ota, M., (1991) Biomaterials, 12, p. 767; Rey, C., Shimizu, M., Collins, B., Glimcher, M.J., (1990) Calcif. Tissue Int., 46, p. 384; Legeros, R.Z., (1993) Clin. Mater., 14, p. 65; Heughebaert, M., Legeros, R.Z., Gineste, M., Guilhem, A., Bonel, G., (1988) J. Biomed. Mater. Res.: Appl. Biomaterials, 22, p. 257; Kieswetter, K., Bauer, T.W., Brown, S.A., Van Lente, F., Merritt, K., (1994) Biomaterials, 15, p. 183; Rey, C., (1995) Actual. Chimique, p. 41; Nancollas, G.H., (1989) Biomineralization. Chemical and Biochemical Perspectives, p. 157. , edited by S. Mann, J. Webb and R. J. P. Williams (VCH, Weinheim, Germany); Bohic, S., Heymann, D., Pouezat, J.A., Gauthier, O., Daculsi, G., (1998) Sciences de la vie, 321, p. 865; Rey, C., Strawich, E., Glimcher, M.J., (1994) Bulletin de l'Institut Océanographique, Monaco, 14, p. 55; Dasarathy, H., Riley, C., Coble, H.D., (1993) J. Biomed. Mater. Res., 27, p. 477; Yamashita, K., Horisaka, Y., Satomura, K., Takagi, T., (1991) Jpn. J. Oral Biol., 33, p. 166; Bonel, G., Heughebaert, J.-C., Heughebaert, M., Lacout, J.L., Lebugle, A., (1988) Ann. N. Y. Acad. Sci., 523, p. 115
Keywords: Apatite; article; Bone; bone mineral; Calcification (biochemistry); Calcium; Carbon; Cellulose; crystal; hydrogel; Hydrogels; hydroxyapatite; Incubation; infrared spectroscopy; mineralization; porosity; priority journal; Scanning electron microscopy; surface property; Swelling; Water

Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits - Lopes, M.A.; Santos, J.D.; Monteiro, F.J.; Ohtsuki, C.; Osaka, A.; Kaneko, S.; Inoue, H. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2001)
In vitro and in vivo bioactivity studies were performed to assess the biocompatibility of CaO-P 2O 5 glass-reinforced hydroxyapatite (GR-HA) composites. The ability to form an apatite layer by soaking in simulated body fluid (SBF) was examined and surfaces were characterized using FTIR reflection and thin-film X-ray diffraction analyses. Qualitative histology, histomorphometric measurements, and push-out testing were performed in a rabbit model for characterizing bone/implant bonding. Under the in vitro conditions using SBF, an apatite layer could not be formed on GR-HA composites within 8 weeks. Results of push-out testing showed bonding between the composites and bone, ranging from 130-145 N after 2 weeks of implantation. After the longest implantation period, 16 weeks, the GR-HA composite prepared with the higher content of CaO-P 2O 5 glass showed the highest bonding force, 606 ± 45 N, compared to 459 ± 30 N for sintered HA. Development of immature bone and modifications in the turnover of a more mature bone on the surface of GR-HA composites were similar to those on sintered HA. © 2000 John Wiley & Sons, Inc. In vitro and in vivo bioactivity studies were performed to assess the biocompatibility of CaO-P 2O 5 glass-reinforced hydroxyapatite (GR-HA) composites. The ability to form an apatite layer by soaking in simulated body fluid (SBF) was examined and surfaces were characterized using FTIR reflection and thin-film X-ray diffraction analyses. Qualitative histology, histomorphometric measurements, and push-out testing were performed in a rabbit model for characterizing bone/implant bonding. Under the in vitro conditions using SBF, an apatite layer could not be formed on GR-HA composites within 8 weeks. Results of push-out testing showed bonding between the composites and bone, ranging from 130-145 N after 2 weeks of implantation. After the longest implantation period, 16 weeks, the GR-HA composite prepared with the higher content of CaO-P 2O 5 glass showed the highest bonding force, 606 ± 45 N, compared to 459 ± 30 N for sintered HA. Development of immature bone and modifications in the turnover of a more mature bone on the surface of GR-HA composites were similar to those on sintered HA. © 2000 John Wiley & Sons, Inc.
Cited By (since 1996): 40Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/1097-4636(20010315)54:4<463::AID-JBM10>3.0.CO;2-YPubMed ID: 11426590Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, INEB, Rua do Campo Alegre, 823, 4150-180 Porto, PortugalChemicals/CAS: Bone Substitutes; Composite Resins; Durapatite, 1306-06-5References: Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Nakamura, T., Kitsugi, T., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J Biomed Mater Res, 24, pp. 471-488;Klein, C.P.A.T., Driessen, A.A., De Groot, K., Van der Hooff, A., Biodegradation behavior of various calcium phosphate materials in bone tissue (1983) J Biomed Mater Res, 17, pp. 769-784; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural Characterization of Glass Reinforced Hydroxyapatite Composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass Reinforced Hydroxyapatite: A Comprehensive Study of the Effect of Glass Composition on the Crystallography of the Composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass Reinforced Hydroxyapatite Composites: Secondary Phases Proportions and Densification Effects on Biaxial Bending Strength (1999) J Biomed Mater Res, 48, pp. 734-740; Lopes, M.A., Saramago, B., Santos, J.D., Monteiro, F.J., Hydrophobicity, Surface Tension and Zeta Potential of Glass Reinforced Hydroxyapatite Composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow Cytometry for Assessing Biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., CaP-rich layer formed on high-strength bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Cho, S.B., Nakanishi, K., Kokubo, T., Soga, N., Ohtsuki, C., Nakamura, T., Kitsugi, T., Yamamuro, T., Dependence of Apatite Formation on Silica Gel on Its Structure: Effect of Heat Treatment (1975) J Am Ceram Soc, 78, pp. 1769-1774; Neo, M., Kotani, S., Fujita, Y., Nakamura, T., Yamamuro, T., Bando, Y., Ohtsuki, C., Kokubo, T., Differences in ceramic-bone interface between surface-active ceramics and resorbable ceramics: A study by scanning and transmission electron microscopy (1992) J Biomed Mater Res, 26, pp. 255-267; Hamson, K.R., Toth, J.M., Stiehl, J.B., Lynch, K.L., Preliminary experience with a novel model assessing in vivo mechanical strength of bone grafts and substitute materials (1995) Calcif Tissue Int, 57, pp. 64-68; Hing, K.A., (1996) Assessment of porous hydroxyapatite for bone replacement, , London: University of London; Albrektsson, T., Johansson, C., Quantitative bone tissue reactions to various metallic materials with reference to the so-called osseointegration concept (1991), pp. 357-363. , Davies JE, editor. The bonebiomaterial interface. Toronto: University of Toronto PressProbster, L., Voigh, C.H., Fuhrman, G., Gross, U.M., Tensile and torsional shear strength of the bone implant interface of titanium implants in the rabbit (1994) J Mater Sci: Mater Med, 5, pp. 314-319; Kokubo, T., Kushitani, H., Ebisawa, Y., Kitsugi, T., Kotani, S., Oura, K., Yamamuro, T., Apatite formation on bioactive ceramics in body environment (1989), 1, pp. 157-162. , Oonishi H, Aoki H, Sawai K, editors. Bioceramics. Tokyo: Ishiyaku EuroAmerica, IncLeGeros, R.Z., (1991), pp. 4-45. , Meyers HM, editor. Calcium phosphates in oral biology and medicine. New York: KargerOhtsuki, C., Kokubo, T., Neo, M., Kotani, S., Yamamuro, T., Nakamura, T., Bando, Y., Bone-Bonding Mechanism of Sintered β-3CaO-P 2O 5 (1991) Phosphorus Research Bulletin, 1, pp. 191-196; Kotani, S., Fujita, Y., Kitsugi, T., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bone bonding mechanism of β-tricalcium phosphate (1991) J Biomed Mater Res, 25, pp. 1303-1315; Lu, J.X., Gallur, A., Flautre, B., Anselme, K., Descamps, M., Thierry, B., Hardouin, P., Comparative study of tissue reactions to calcium phosphate ceramics among cancellous, cortical, and medullar bone site in rabbits (1998) J Biomed Mater Res, 42, pp. 357-367; Kitsugi, T., Nakamura, T., Oka, M., Senaha, Y., Goto, T., Bonebonding behavior of plasma-sprayed coatings of bioglass, AW-glass ceramic, and tricalcium phosphate on titanium alloy (1996) J Biomed Mater Res, 30, pp. 261-269; Kitsugi, T., Yamamuro, T., Nakamura, T., Kotani, S., Kokubo, T., Takeuchi, H., Four calcium phosphate ceramics as bone substitutes for non-weight-bearing (1993) Biomaterials, 14, pp. 216-224; De Lauge, G.L., De Putter, C., De Wijs, F.L.J.A., Histological and ultrastructural appearance of the hydroxy apatite-bone interface (1990) J Biomed Mater Res, 24, pp. 829-845; Yamada, S., Nakamura, T., Kokubo, T., Oka, M., Yamamuro, T., Degradation of the apatite layer formed on bioactive ceramics and the underlying ceramic surface by osteoclasts in a culture system (1994) Cells and Materials, 4, pp. 347-356; Brunski, J.B., Influence of biomechanical factors at the bone-biomaterial interface (1990), pp. 391-405. , Davies JE, editor. The bone-biomaterial interface. Toronto: University of Toronto PressDhert, J.A., Thomsen, P., Blomgren, A.K., Esposito, M., Ericson, L.E., Verbout, A.J., Integration of press-fit implants in cortical bone: A study on interface kInetics (1998) J Biomed Mater Res, 41, pp. 574-583; Gao, T.J., Lindholm, T.S., Kommonen, B., Ragni, P., Paronzini, A., Lindholm, T.C., Microscopic evaluation of bone-implant contact beween HA, bioactive glass and tricalcium phosphate implanted in sheep diaphyseal defects (1995) Biomaterials, 16, pp. 1175-1179; Oonishi, H., Hench, L.L., Wilson, J., Sugihara, F., Tsuji, E., Kushitani, S., Iwaki, H., Comparative bone growth behavior in granules of bioceramic materials of various sizes (1999) J Biomed Mater Res, 44, pp. 31-43; Marie, P.J., De Vernejoul, M.C., Lomri, A., Stimulation of bone formation in osteoporosis patients treated with fluoride associated with increased DNA synthesis by osteoblast cells in vitro (1992) J Bone Miner Res, 7, pp. 103-113; Rodan, G.A., Introduction to bone biology (1992) Bone, 13, pp. S3-S6
Keywords: animal experiment; animal tissue; Animals; article; Biocompatibility; Body fluids; Bonding; Bone; Bone Substitutes; bone turnover; Ceramic materials; Composite Resins; Durapatite; Fiber reinforced materials; Fourier transform infrared spectroscopy; glass; Glass reinforced hydroxyapatite composites; Glass-reinforced hydroxyapatite composites; Histological studies; histology; Histomorphometric measurements; hydroxyapatite; implant; implantation; Implants (surgical); In vitro bioactivity; In vivo evaluation; Interfaces (materials); male; nonhuman; orthopedic equipment; ossification; Prosthesis Implantation; Push out testing; Push-out testing; rabbit; Rabbits; Spectroscopy, Fourier Transform Infrared; Stress, Mechanical; Surgical equipment; tibia; Time Factors; X ray diffraction; X ray diffraction analysis

Silicon nitride - bioglass composite for biomedical applications - Santos, J.D.; Amaral, M.; Oliveira, S.M.; Lopes, M.A.; Silva, R.F. (Key Engineering MaterialsKey Eng Mat, 2001)
This study aimed at preparing novel highly toughened bioactive ceramic composite composed of Si 3N 4 matrix and Bioglass using a hot pressing technique. Densification rate, hardness and fracture toughness of this novel composite were assessed as well as in vitro bioactivity using a simulated body fluid (SBF). A fracture toughness of 5.2±0.3 MPa.m. 1/2 was achieved for fully densified samples, which complies with K 1c value reported for cortical bone. This novel composite, which can be used in high load medical applications, seems to overcome the drawback of low fracture toughness presented by most currently available bioactive ceramics.
Conference code: 57760Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Universidade do Porto, Porto, PortugalReferences: Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics;(1995) Engineering Materials Handbook, Ceramics and Glasses, Asm International, 4, pp. 812-820; Fishman, G., Clare, A., Hench, L.L., (1995) Materials and Applications, 48; Niihara, K., Morena, R., Hasselman, D.P., (1982) J. Mater. Sci., 1, pp. 13-16; Hench, L.L., (1998) Bioceramics, J. Am. Ceram. Soc., 81 (7), pp. 1705-1728; Landis, W.J., Martin, J.R., (1984) J. Vac. Sci. Technol., A2, p. 1108
Keywords: Bioactive ceramic composite; Bioglass; Biomaterials; Body fluids; Bone; Ceramic matrix composites; cortical bone; Densification; Fracture toughness; Glass ceramics; Hot pressing; Medical applications; Silicon nitride; Simulated body fluid

Starch based copolymers as biomaterials in vivo biocompatibility study - Souillac, V.; Fricain, J.C.; Bareille, R.; Reis, R.L.; Chauveaux, D.; Baquey, C. (Key Engineering MaterialsKey Eng Mat, 2001)
This report is a preliminary study of a starch-based copolymer that was used as a bone substitute. The interest of this study was to evaluate the possibility of using a hydrophilic material as a bone substitute. We studied this copolymer alone, after phosphorylation, and after hydroxyapatite coating.
Conference code: 57760Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Souillac, V.; Universite Bordeaux 2, Bordeaux, FranceReferences: Hollinger, J.O., Brekke, J., Gruskin, E., Lee, D., (1996) Clin. Orthop., 324, p. 55;Nizard, R., Bizot, P., Sedel, L., (1996) Encycl. Med. Chir., Orthopédie-traumatologie, 44 (3). , 20p; Delécrin, J., Dupraz, A., Passuti, N., (1996) Cahiers D'enseignement de la SOFCOT, 57, p. 97; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Adv. Technol., 7, p. 784; Kokubo, T., Hata, K., Nakamura, T., Yamamuro, T., (1991) Bioceramics, 4, p. 113. , UK; Reis, R.L., Cunha, A.M., Fernandes, M.H., (1997) J. Mater. Sci. : Mater, in Medecine, 8, p. 897; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Harmand, M.F., (1993) In Vitro Cell Dev. Biol., 29, p. 699; Parish, C.R., Mullbacher, A., (1983) J. Immunol. Meth., 58, p. 225; Mosmann, T., (1983) J. Immunol. Meth., 65, p. 55; Koshino, T., Kubota, W., Morii, T., (1995) Biomaterials, 16, p. 125; Pasquier, G., Flautre, B., Blary, M.C., Anselme, K., Hardouin, P., (1996) Journal of Materials Science, 7, p. 683; Nagano, M., Kitsugi, T., Nakamura, T., Kokubo, T., Tanahashi, M., (1996) J. Biomed. Mater. Res., 31, p. 487; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., (1989) J. Biomed. Mater. Res., 23, p. 125
Keywords: Biocompatibility; Bone; Bone substitute; Copolymers; Ethanol; Ethylene; hydroxyapatite; Hydroxyapatite coating; Implants (surgical); orthopedics; Phosphates; phosphoric acid; Phosphorylation; Starch; Substitution reactions; Vinyl resins

Stearyl poly(ethylene oxide) grafted surfaces for preferential adsorption of albumin - Ji, J.; Feng, L.; Barbosa, M.A. (BiomaterialsBiomaterials, 2001)
An ideal surface for many biomedical applications would resist non-specific protein adsorption while at the same time triggering a specific biological pathway. Based on the approach of selectively binding albumin to free fatty acids, stearyl groups were immobilized onto poly(styrene) backbone via poly(ethylene oxide) side chains. X-ray photoelectron spectroscopy (XPS) analysis indicates substantial surface enrichment of the stearyl poly(ethylene oxide) (SPEO). In an aqueous environment, the surface rearrangement is limited, as proved by dynamic contact angle tests. The comb-like copolymer presents a special hydrophobic surface with high SPEO surface density, which may be due to the 'tail like' SPEO architecture at the copolymer/water interface. Protein adsorption tests confirm that the comb-like surfaces adsorb high levels of albumin and resist fibrinogen adsorption very significantly. The surfaces prepared in this research attract and reversibly bind albumin due to the synergistic action of the PEO chains and the stearyl end groups. Copyright © 2001 Elsevier Science Ltd.
Cited By (since 1996): 26Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00048-5PubMed ID: 11575476Language of Original Document: EnglishCorrespondence Address: Ji, J.; Department of Polymer Science, Zhejiang University, Hangzhou 310027, China; email: @@@Chemicals/CAS: Biocompatible Materials; Fibrinogen, 9001-32-5; Ligands; polyethylene glycol-polystyrene; Polyethylene Glycols; Polystyrenes; Serum Albumin; Stearates; stearyl poly(ethylene oxide)References: Andrade, J.D., Nagaoka, S., Cooper, S., Okano, T., Kim, S.W., Surface and blood compatibility; current hypothesis (1987) ASAIO Trans, 33 (2), pp. 75-76;Ranter, B.D., The engineering of biomaterials exhibiting recognition and specificity (1996) J Mol Recognition, 9, pp. 617-625; Jeon, S.I., Lee, J.H., Andrade, J.D., De Gennes, P.G., Protein-surface interactions in the presence of polyethylene oxide (1991) J Colloid Interface Sci, 142 (1), pp. 149-158; Merrill, E.W., Salzman, E.W., Polyethylene oxide as a biomaterial (1983) ASAIO J, 6, pp. 60-64; Amiji, M., Park, K., Prevention of protein adsorption and platelet adhesion on surfaces by PEO/PPO/PEO triblock copolymers (1992) Biomaterials, 13, pp. 682-692; Mayes, A.M., Irine, D.J., Tailoring polymer surface for control cell behavior (1998), pp. 73-84. , Thomson G., Mooney R.C., Healy D.J., Ikada K.E., Mikos Y. (Eds.), Biomaterials regulating cell function and tissue development, Warrendale, PA: MRSKeogh, R.J., Eaton, J.W., Albumin binding surfaces for biomaterials (1994) J Lab Clin Med, 124 (4), pp. 537-545; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., Alkyl substituted polymers with enhanced albumin affinity (1981) Trans Am Soc Artif Intern Organs, 27, pp. 499-503; Pitt, W.G., Cooper, S.L., Albumin adsorption on alkyl chain derivatized polyurethane; I. The effect of C-18 alkylation (1988) J Biomed Mater Res, 22, pp. 359-382; Frautschi, J.R., Munro, M.S., Lloyd, D.R., Eberhart, R.C., Alkyl derivatized cellulose acetate membranes with enhanced albumin affinity (1983) Trans Am Soc Artif Intern Organs, 29, pp. 242-244; Keogh, J.R., Velander, F.F., Eaton, J.W., Albumin-binding surface for implantable devices (1992) J Biomed Mater Res, 26, pp. 441-456; Qiu, Y.X., Yu, X.J., Feng, L.X., Yang, S.L., Synthesis and characterization of amphiphilic and microphase-separated graft copolymer (1992) Makromol Chem, 173, p. 1377; Gallo BM, Russo S. In: Platzer NAJ, editor. Copolymer, polymers and composites. Washington, DC, 1975. p. 85Neumann AW, Good RJ. In: Good RJ, Stromberg RR, editors. Surface and colloid science, vol. 11, Experimental methods. New York: Plenum Press, 1979. p. 31Brash, J.L., Davidson, V.J., Adsorption of glass and polyethylene from solutions of fibrinogen and albumin (1976) Thromb Res, 9 (3), pp. 249-259; Lide DR. In: Lider DR, editor. Surface tension of common liquids, Handbook of chemistry and physics. Boca Raton, FL: CRC Press, 1996. p. 6-147Carel, J.V.O., (1994), pp. 170-177. , Carel J.V.O. (Ed.), Interfacial forces in aqueous media, New York: Marcel DekkerMori, Y., Nagaoka, S., Takiuchi, H., Kikuci, T., Noguchi, N., Tanzawa, H., Noishili, Y., A new antithrombogenic material with long polyethyleneoxide chains (1982) Trans Am Soc Artif Intern Organs, 28, pp. 459-463; Wu, D., Jian, K., (1995) Sci China (B), 25 (11), p. 1121; Wu, D., Jian, K., (1995) Sci China (B), 26 (5), p. 409; Walton, D.G., Soo, P.P., Mayes, A.M., Sofia Allgor, S.J., Fujii, J.T., Griffith, L.G., Ankner, J.F., Satija, S.K., Creation of stable poly(ethylene oxide) surfaces on poly(methyl methacrylate) using blends of branched and linear polymer (1997) Macromolecules, 30 (22), pp. 6947-6956; Walton, D.G., Mayes, A.M., Entropically driven segregation in blend of branched and liner polymers (1996) Phys Rev E, 54 (3), pp. 2811-2815
Keywords: Adsorption; Albumin; Amphiphilic copolymer; article; Biocompatible Materials; Biomedical engineering; Catalyst selectivity; Cell immobilization; Contact angle; copolymer; Copolymers; density; Electron Probe Microanalysis; fibrinogen; Grafting (chemical); Humans; hydrophobicity; Ligands; macrogol; macrogol derivative; materials testing; Polyethylene Glycols; Polystyrenes; priority journal; Protein adsorption; protein binding; Proteins; roentgen spectroscopy; Serum Albumin; Stearates; Stearyl end groups; Surface Properties; surface property; Ultraviolet spectroscopy; X ray photoelectron spectroscopy

Brazing parameters determine the degradation and mechanical behaviour of alumina/titanium brazed joints - Paiva, O.C.; Barbosa, M.A. (Journal of Materials ScienceJ Mater Sci, 2000)
The main aims of the present study are simultaneously to relate tho brazing parameters with the correspondent interfacial microstructure, the resultant mechanical properties and the electrochemical degradation behaviour of commercially pure titanium/alumina brazed joints. A filler metal on the Ag-26.5Cu-3Ti system has been used. Three different brazing temperatures (850, 900 and 950 °C) and three holding times (0.3, 1.2, 2.4 ks) were tested, in order to understand the influence of each combination of brazing temperature holding times, over the final microstructure and properties of the joints. The mechanical properties of the M/C joints were assessed on the basis of bond strength tests carried out using a shear solicitation scheme. The fracture surfaces were studied morphologically and structurally using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and X-ray diffraction analysis (XRD). The degradation behaviour of the M/C joints was assessed by means of electrochemical techniques. It was found that a brazing temperature of 850 °C and a holding time of 2.4 ks, produces the best results in terms of bond strength, 130±16 MPa. The mechanical properties obtained could be explained on the basis of the different compounds identified on the fracture surfaces by XRD. On the other hand, a brazing temperature of 950 °C produces the best results in terms of corrosion rates (lower corrosion current), 3.44±0.73 μA cm
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JMTSAdoi: 10.1023/A:1004776117823Language of Original Document: EnglishCorrespondence Address: Paiva, O.C.; Inst de Engenharia Biomedica, Porto, PortugalReferences: Samandi, M., Gudze, M., Evans, P., Nucl, (1997) Instr. and Meth. in Phys. Res. B, 127-128, p. 669;Paiva, O.C., Barbosa, M.A., (1997) J. Mater. Sci., 32, p. 653; Moret, F., Eustathopoulos, N., (1993) J. Physique IV, 3, p. 1043. , Colloque C7; Suganuma, K., Okamoto, T., Koizumi, M., Shimada, M., (1985) J. Amer. Ceram. Soc., 68, pp. C334; Cao, H.C., Thouless, M.D., Evans, A.G., (1988) Acta Metall. Matter., 36, p. 2037; Hao, H., Wang, Y., Jin, Z., Wang, X., (1995) J. Amer. Ceram. Soc., 78, p. 2157; Yamada, T., Yokoi, K., Kohno, J., (1990) J. Mater. Sci., 25, p. 2188; Elssener, G., (1990) Joining of Ceramics, p. 128. , edited by M. G. Nicholas Chapman and Hall, London; Hao, H., Wang, Y., Jin, Z., Wang, X., (1995) J. Mater. Sci., 30, p. 4107; Suganuma, K., Okamoto, T., Koizumi, M., Shimada, M., (1985) J. Mater. Sci., 20, p. 648; Xian, A.P., Si, Z.Y., (1992) J. Mater. Sci., 27, p. 1560; Locatelli, M.R., Dalgleish, B.J., Nakashima, K., Tomsia, A.P., Glaeser, A.M., (1997) Ceramics International, 23, p. 313; Suganuma, K., (1990) Joining of Ceramics, p. 173. , edited by M. G. Nicholas Chapman and Hall, London; Murakawa, H., Ueda, Y., (1989) Trans. JWRI, 18, p. 295; Zhai, Y., North, T.H., Ren, J., (1997) J. Mater. Sci., 32, p. 1399; Nicholas, M.G., (1990) Joining of Ceramics, p. 73. , edited by M. G. Nicholas Chapman and Hall, London; Peteves, S.D., Ceccone, G., Paulasto, M., Stamos, V., Yvon, P., (1996) JOM, 48, p. 48; Li, J.G., (1994) Ceramics International, 20, p. 391; Loehman, R.E., Tomsia, A.P., (1992) Acta Metall. Mater., 40 (SUPPL.), pp. S75; Schwartz, M.M., (1990) Ceramic Joining, p. 75. , edited by M. M. Schwartz, ASM International, Ohio; Paiva, O.C., Barbosa, M.A., (1997) High Temperature Capillarity, p. 306. , edited by N. Eustathopoulos and N. Sobczak Foundry Research Institute, Cracow, Poland; Rocha, L.A., Barbosa, M.A., Puers, R., (1995) J. of Mater. Sci.: Mater. in Med., 6, p. 835; Idrissi, H., Audisio, S., Elmouaffek, S., Chastrette, M., (1987) Materiaux et Techniques, 10, p. 433; Idrissi, H., Millet, J.P., Audisio, S., Irhzo, A., (1994) J. of Mater. Science, 29, p. 5327; Niu, Y., Gesmundo, F., Viani, F., Wu, W., (1997) Oxidation of Metal, 47, p. 21; Stern, M., Geary, A.L., (1957) Corrosion, 13, p. 139; Paiva, O.C., Ferreira, L., Barbosa, M.A., (1998) Interfacial Science in Ceramics Joining, p. 329. , edited by A. Bellosi, T. Kosmac and A. P. Tomsia, NATO ASI Series, Kluwer Academic Publishers, Netherlands; Gubbels, G.H.M., Heikinheimo, L.S.K., Klomp, J.T., (1994) Z. Metall., 85, p. 828; Naka, S., Thomas, M., Khan, T., (1996) La Recherche Aérospatiale, 5-6, p. 373; (1992) Powder Diffraction File, , ASTM, Philadelphia, PA; Kolman, D.G., Scully, J.R., (1996) J. Electrochem. Soc., 143, p. 1847; Yau, T.E.-L., (1992) Werkstoffe und Korrosion, 43, p. 358; Sequeira, C.A.C., (1995) British Corrosion Journal, 30, p. 137; Uhlig, H.H., (1967) Corrosion and Corrosion Control, , John Wiley & Sons, New York; Paiva, O.C., Barbosa, M.A., (1998) Bioceramics, 11, p. 699. , edited by R. Z. LeGeros and J. LeGeros World Scientific Publishing Co. Pte. Ltd., Singapore
Keywords: Alumina; Aluminum copper titanide; Brazing filler metals; Ceramic matrix composites; Degradation; Energy dispersive spectroscopy; fracture; Joints (structural components); Scanning electron microscopy; Silver alloys; Titanium; X ray diffraction analysis

Classification of breast tissue by electrical impedance spectroscopy - Estrela Da Silva, J.; Marques De Sá, J.P.; Jossinet, J. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 2000)
Electrical impedance spectroscopy is a minimally invasive technique that has clear advantages for living tissue characterisation owing to its low cost and ease of use. The present paper describes how this technique can be applied to breast tissue classification and breast cancer detection. Statistical analysis is used to derive a set of rules based on features extracted from the graphical representation of electrical impedance spectra. These rules are used hierarchically to discriminate several classes of breast tissue. Results of statistical classification obtained from a data set of 106 cases representing six classes of excised breast tissue show an overall classification efficiency of ~92% with carcinoma discrimination > 86%.Electrical impedance spectroscopy is a minimally invasive technique that has clear advantages for living tissue characterization owing to its low cost and ease of use. The present paper describes how this technique can be applied to breast tissue classification and breast cancer detection. Statistical analysis is used to derive a set of rules based on features extracted from the graphical representation of electrical impedance spectra. These rules are used hierarchically to discriminate several classes of breast tissue. Results of statistical classification obtained from a data set of 106 cases representing six classes of excised breast tissue show an overall classification efficiency of approximately 92% with carcinoma discrimination >86%.
Cited By (since 1996): 42Export Date: 21 November 2012Source: ScopusCODEN: MBECDPubMed ID: 10829386Language of Original Document: EnglishCorrespondence Address: Marques de Sa, J.P.; INEB, Facul. Engenharia Universidade Porto, Porto, Portugal; email: jmsa@fe.op.ptReferences: Brown, B.H., Barber, D.C., Morice, A.H., Leathard, A.D., Cardiac and respiratory related electrical impedance changes in the human thorax (1994) IEEE Trans. Biomed. Eng., BME-41, pp. 729-734;Campbell, A.M., Land, D.V., Dielectric properties of female breast tissue measured in vitro at 3.2 GHz (1992) Phys. Med. Biol., 37, pp. 193-210; Duda, R., Hart, P., (1973) Pattern Classification and Scene Analysis, , Wiley, New York; Foley, D.H., Considerations of sample and feature size (1972) IEEE Trans. Inform. Theory, IT-18, pp. 618-626; Foster, K.R., Schwan, H.P., Dielectric properties of tissues and biological materials: A critical review (1989) CRC Crit. Reviews Biomed. Eng., 17, pp. 25-104; Fukunaga, K., (1972) Introduction to Statistical Pattern Recognition, , Academic Press, New York and London; Gersing, E., Schäfer, M., Osypka, M., The appearance of positive phase angles in impedance measurements on extended biological subjects (1995) Innov. Techn. Biol. Med., 16 (SPEC. ISSUE 2), pp. 72-76. , Proc. 'CAIT Workshop on Electrode-Skin Interface in EIT'; Heinitz, J., Minet, O., Dielectric properties of female breast tumors (1995) Proc. '9th Int. Conf. Electrical Bioimpedance', pp. 356-359. , University of Heidelberg Press; Henderson, R.P., Webster, J.G., An impedance camera for spatially specific measurements of the thorax (1978) IEEE Trans. Biomed. Eng., BME-27, pp. 250-254; Jossinet, J., Variability of impedivity in normal and pathological breast tissue (1996) Med. Biol. Eng. Comput., 34, pp. 346-350; Jossinet, J., The impedivity of freshly excised human breast tissue (1998) Physiol. Meas., 19, pp. 61-75; Jossinet, J., Lavandier, B., The discrimination of excised cancerous breast tissue samples using impedance spectroscopy (1998) Bioelectrochem. Bioenerg., 45, pp. 161-167; Kubicek, W.G., Patterson, R.P., Witsoe, D.A., Impedance cardiography as a noninvasive method of monitoring cardiac function and other parameters of the cardiovascular system (1970) Ann. N.Y. Acad. Sciences, 170, pp. 24-732; Morimoto, T., Kinouchi, Y., Iritani, T., Kimura, S., Konishi, Y., Mitsuyama, N., Komaki, K., Monden, Y., Measurement of the electrical bio-impedance of breast tumors (1990) Eur. Surg. Res., 22, pp. 86-92; Raudys, S., Pikelis, V., On dimensionality, sample size, classification error and complexity of classification algorithm in pattern recognition (1980) IEEE Trans. Patt. Anal. Mach. Intel., PAMI-2, pp. 242-252; Shapiro, S.S., Wilk, S.S., Chen, S.W., A comparative study of various tests for normality (1968) J. Am. Stat. Ass., 63, pp. 1343-1372; Swain, P.H., The decision tree classifier: Design and potential (1977) IEEE Trans. Geosci. Electronics, GE-15, pp. 142-147; Schwan, H.P., Alternating current spectroscopy of biological substances (1959) Proc. IRE, 47, pp. 1841-1855; Surowiec, A.J., Stuchly, S.S., Barr, J.R., Swarup, A., Dielectric properties of breast carcinoma and the surrounding tissues (1988) IEEE Trans. Biomed. Eng., BME-35, pp. 257-263; Tachibana, S., Aguilar, J.A., Birzis, L., Scanning the interior of living brain by impedography (1970) J. of App. Physiol., 28, pp. 534-539
Keywords: article; Breast; breast cancer; Breast Neoplasms; cancer classification; Data classification; Discriminant Analysis; Electric Impedance; Electrical impedance spectroscopy; Electrodiagnosis; Feature extraction; Female; human; Humans; impedance; Impedance spectroscopy; major clinical study; Medical imaging; Signal Processing, Computer-Assisted; Spectroscopy; Statistical analysis; Statistical methods; Tissue; Tissue characterisation

A computational model of visual cortex receptive fields using spatio-temporal filters - Milanova, M.G.; Elmaghraby, A.S.; Wachowiak, M.P.; Campilho, A. (Proceedings of the IEEE/EMBS Region 8 International Conference on Information Technology Applications in Biomedicine, ITABProc IEEE EMBS Reg 8 Int Conf Inf Technol Appl Biomed ITAB, 2000)
It is known that neurons in the primary visual cortex are characterized by receptive fields that are selective for specific spatial orientations. It is believed that the sense of object motion and velocity are also related to these fields, as objects in natural scenes are represented by a sparse set of statistically independent components, such as edges. Currently, computational models of receptive fields consider only spatial components, and thus cannot account for time-varying sensory stimuli. In this paper, a model based on independent components analysis and cellular neural networks is proposed. This approach extends existing models to incorporate temporal aspects of sequences of images of natural scenes.
Conference code: 58015Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Milanova, M.G.; INEB, Inst. of Biomedical Engineering, University of Porto, Praça Coronel Pacheco, 1 4050 Porto, Portugal; email: milanova@ineb.fe.up.ptReferences: Hubel, D.H., Wiesel, T.N., Receptive fields, binocular interaction, and functional architecture in the cat's visual cortex (1962) Journal of Physiology (London), 160, pp. 106-154;DeAngelis, G.C., Ohzawa, I., Freeman, R.D., Receptive-field dynamic in the central visual pathways (1995) Trends in Neuroscience, 18, pp. 451-458; Atick, J., Redlich, N., What does the retina know about natural scenes? (1992) Neural Computation, 4, pp. 196-210; Barlow, H.B., What is the computational goal of the neocortex? (1994) Large-Scale Neuronal Theories of the Brain, pp. 1-22. , C. Koch and J. L. Davis, eds, Cambridge, MA, MIT Press; Olshausen, B.A., Field, D.J., Emergence of simple-cell receptive field properties by learning a sparse code for natural images (1996) Nature, 381, pp. 607-609; Rao, R.P.N., Ballard, D.H., Dynamic model of visual recognition predicts neural response properties in the visual cortex (1997) Neural Computation, 9, pp. 721-763; Olshausen, B.A., (2000) Sparse coding of time-varying natural images, , http://psyweb.ucdavis.edu/olshausen; Oja, E.E., Neural networks, principal components and subspaces (1989) International Journal of Neural Systems, 1, pp. 61-68; Field, D.J., What is the goal of sensory coding? (1994) Neural Computation, 6, pp. 559-601; Field, D.J., Relations between the statistics of natural images and the response properties of cortical cells (1987) J. Opt. Soc. Am.A, 4, pp. 2379-2394; Bell, A.J., Sejnowski, T.J., The independent components of natural scenes are edge filters (1997) Vision Research, 37, pp. 3327-3338; Smith, A.T., Snowdon, R.S., (1994) Visual Detection of Motion, , Academic Press Inc., San Diego; Zemel, R.S., Sejnowski, T.J., A model for encoding multiple object motions and self-motion in area MST of primate visual cortex (1998) Journal of Neuroscience, 18, pp. 531-547; Van Hateren, J.H., Ruderman, D.L., Independent component analysis of natural image sequences yields spatio-temporal filters similar to simple cells in primary visual cortex (1998) Proc. Royal Soc. London B, 265, pp. 2315-2320; Jones, J.P., Palmer, L.A., The two-dimensional spatial structure of simple receptive fields in cat striate cortex (1987) Journal of Neurophysiology, 58, pp. 1187-1211; Jones, J.P., Palmer, L.A., An Evaluation of the two-dimensional Gabor filter model of simple receptive fields in cat striate cortex (1987) Journal of Neurophysiology, 58, pp. 1233-1258; Jones, J.P., Stepnoski, A., Palmer, L.A., The two-dimensional spectral structure of simple receptive fields in cat striate cortex (1987) Journal of Neurophysiology, 58, pp. 1212-1232; Lewicki, M.S., Olshausen, B.A., Probabilistic framework for the adaptation and comparison of image codes (1999) Journal of the Optical Society of America, 16, pp. 1587-1601; Chua, L.O., Yang, L.L., Cellular Neural Networks: Theory and Applications (1988) IEEE Trans. on Circuits and Systems, 35, pp. 1257-1290 Sponsors: IEEE
Keywords: Cellular neural networks; Computational methods; ICA; Independent component analysis; Mathematical models; Neurology; Receptive fields; Receptive fields (RF); Spatial filters; Spatio-temporal filters; Visual modeling

Concept, design and fabrication of smart orthopedic implants - Burny, F.; Donkerwolcke, M.; Moulart, F.; Bourgois, R.; Puers, R.; Van Schuylenbergh, K.; Barbosa, M.; Paiva, O.; Rodes, F.; Bégueret, J.B.; Lawes, P. (Medical Engineering and PhysicsMed. Eng. Phys., 2000)
Extensive clinical experience has been built up using orthopaedic implants instrumented with strain gauges connected to a Wheatstone bridge by means of percutaneous leads. This research showed the medical relevance of the monitoring of the deformation of implants as a powerful tool to evaluate nursing and rehabilitation exercises, for tracing dangerous overloads and anticipating implant failure and also to observe the healing process. The IMPACT 3500 project focuses on the instrumentation of femoral implants with on board sensors: regular Benoist-Girard implants have been modified, to contain a 'sensing cell', and thoroughly tested in vitro and in vivo. The implant deformations are measured with resistive strain gauges, and the signal is transferred to a personal computer for processing and display, via a hard wired connection, or via a telemetry system. Two fully implantable wireless designs, called Linkstrain and Sealstrain, are powered from the outside by magnetic induction. As Sealstrain contains the whole telemetric system in its cavity, the highest miniaturization was required; this seriously deteriorates the efficiency of the inductive power link. © 2001 IPEM.
Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: MEPHEdoi: 10.1016/S1350-4533(00)00062-XPubMed ID: 11165144Language of Original Document: EnglishCorrespondence Address: Burny, F.; Service d'Orthopedie-Traumatologie, Cliniques Universitaires Bruxelles, Hôpital Erasme, Brussels, Belgium; email: fburny@ulb.ac.beChemicals/CAS: Biocompatible Materials; Ceramics; Metals; Stainless Steel, 12597-68-1References: Burny, F., Donkerwolcke, M., Moulart, F., Clinical application of the monitoring of orthopedic implants (1993), pp. 138-146. , Burny R, Puers F, editors. Monitoring of orthopedic implants. A biomaterials microelectronics - challenge. Amsterdam: ElsevierBurny, F., Zucman, J., Bourgois, R., Aubriot, J.H., Sedel, J., Utilisation des jauges extensométriques pour la mesure de la consolidation des fractures du tibia traitées par enclouage centromédullaire. Etude théorique et premiers résultats (1971) Acta Orthop Belg, 37, pp. 266-277;Moulart, F., (1975) Rééducation des fractures hautes du fémur. Mesure des déformations du matériel d'ostéosynthese, , Mémoire de Licence en Kinésithérapie, Université Libre de Bruxelles; Burny, F., Moulart, F., Hinsenkamp, M., Traitement des fractures métastatiques de la region sous-trochantérienne. Etude biomécanique; cas cliniques (1976) Acta Orthop Belg, 42, pp. 31-41; Burny, F., Donkerwolcke, M., Telemetry in the musculoskeletal system (1991), pp. 391-394. , Payne PA, editor. Concise encyclopedia of biological and biomedical measurement systems. Oxford: Pergamon PressPuers, R., Burny, F., Biotelemetry in orthopaedics (1992), 3, pp. 285-306. , Muster D. et al., editors. European Materials Research Society Monographs. Biomaterials. Hard Tissue Repair and Replacement, Amsterdam: ElsevierKadefors, R., Kaiser, E., Petersen, I., Energizing implantable transmitters by means of coupled inductance coils (1969) IEEE Trans Biomed Eng, 16 BME, pp. 177-183; Ko, W.H., Liang, S.P., Fung, C.D.F., Design of radio-frequency powered coils for implant intruments (1977) Med Biol Eng Comput, 15, pp. 634-640; Donaldson, N., De, N., Perkins, T.A., Analysis of resonant coupled coils in the design of radio frequency trancutaneous links (1983) Med Biol Eng Comput, 21, pp. 612-627; Grossman, D.G., Machining a machinable glass-ceramic (1978) Vacuum, 28, pp. 55-61; Van Schuylenbergh, K., Puers, R., The influence of moisture leakage on implant strain measurements with resistive strain gauges (1993), pp. 125-137. , Burny R, Puers F, editors. Monitoring of orthopedic implants. A biomaterials microelectronics - challenge. Amsterdam: ElsevierWranglén, G., (1985) An introduction to corrosion and protection of metals, , London: Chapman & Hall; Barbosa, M.A., Surface layers and the reactivity of metallic implants (1992), pp. 257-284. , Muster D, editor. Biomaterials - hard tissue repair and replacement, E-MRS Monographs. North-Holland: Elsevier ScienceNicholas, M.G., Active metal brazing (1986) British Ceramic Transactions Journal, 85, pp. 144-146; Pattee, H.E., Joining ceramics to metals and other materials (1972) Welding Research Council Bulletin, 178, pp. 2435-2442. , New York; Nicholas, M.G., Crispin, R.M., Brazing ceramics with alloys containing titanium (1989) Ceramic Engineering and Science Proceedings, 10, pp. 1602-1612; Rodes, F., Zardini, C., Devall, Y., Puers, R., Van Schuylenbergh, K., Burny, F., Donkerwolcke, M., Moulart, F., Direct digitization of low level transducer outputs for low power intracorporal telemetry systems (1993), pp. 401-409. , Mancini P, Fioretti S, editors. 12th Int. Symposium on Biotelemetry, Ancona. Pisa, Italy: Universitaria Litografia FeliciFlack, F.C., James, E.D., Schlapp, D.M., Mutual inductance of air-cored coils: Effect on design of radio-frequency coupled implants (1971) Med Biol Eng Comput, 9, pp. 79-85;
Keywords: article; atomic absorption spectrometry; Biocompatible Materials; biomechanics; body movement; Bone Plates; ceramics; compression; Corrosion; Failure of implants; Femoral Fractures; femur; Fracture healing; healing; Humans; materials testing; metal; metal implantation; Metals; microcomputer; Microscopy, Electron, Scanning; Monitoring, Physiologic; Orthopedic implants; orthopedic surgery; priority journal; Prostheses and Implants; Prosthesis Design; prosthesis failure; Rehabilitation; Scanning electron microscopy; sensor; Sensors; Smart implants; Spectrum Analysis; Stainless steel; strain gauge transducer; Strain measurements; Stress, Mechanical; Telemetry; Weight-Bearing

Crystallization and microstructure analysis of calcium phosphate-based glass ceramics for biomedical applications - Zhang, Y.; Santos, J.D. (Journal of Non-Crystalline SolidsJ Non Cryst Solids, 2000)
Calcium phosphate glasses and glass ceramics (CaO/P 2O 5 = 1.25 in molar ratio) modified by small amounts of additives such as Na 2O, MgO, TiO 2 and ZrO 2 were prepared after appropriate heat treatment for nucleation and crystallization. Based upon differential thermal analysis (DTA) results, a two-step heat treatment was used for crystal nucleation and growth. X-ray diffraction (XRD) analysis demonstrated that bioresorbable β-Ca 2P 2O 7 (β-DCP), β-Na 2CaP 2O 7, Na 2Mg(PO 3) 4 phases were formed in the glass matrix depending upon the relative contents of the additives. By adding higher contents of Na 2O and TiO 2 and using CaO/P 2O 5 = 1.5-2.0, crystallization of β-DCP and Ca 3(PO 4) 2 (β-TCP), and the formation of a dense structure in the glass ceramics were obtained. The precipitation of these crystals could be well distinguished at a magnification of 4000× and phases were dispersed in areas of micron size. A porous structure may be easily formed after the soluble phases are dissolved in physiological media. These glass ceramics with high CaO/P 2O 5 ratio, modified by the above mentioned additives are expected to find use as implants for bone replacement/regeneration and drug delivery carriers synergistically, because the soluble phases may act as drug delivery carriers and the porous structure will allow for bone ingrowth.
Cited By (since 1996): 42Export Date: 21 November 2012Source: ScopusCODEN: JNCSBdoi: 10.1016/S0022-3093(00)00115-0Language of Original Document: EnglishCorrespondence Address: Zhang, Yong; Inst de Engenharia Biomedica, Porto, PortugalReferences: Kitsugi, T., Yamamuro, T., Nakamura, T., Kotani, S., Kokubo, T., Takeuchi, H., (1993) Biomaterials, 14, p. 216;Kitsugi, T., Yamamuro, T., Nakamura, T., Oka, M., (1995) Biomaterials, 16, p. 1101; Doremus, R.H., (1992) J. Mater. Sci., 27, p. 285; Kokubo, T., (1993) An Introduction to Bioceramics, p. 75. , in L.L. Hench Wilson J. (Eds.), World Scientific, Singapore; Tracy, B., Doremus, R.H., (1984) J. Biomed. Mater. Res., 18, p. 719; Jha, L.J., Best, S.M., Santos, J.D., Bonfield, W., (1997) J. Mater. Sci.: Mater. Med., 8, p. 185; Hench, L.L., (1991) J. Am. Ceram. Soc., 74, p. 1487; Hench, L.L., Anderson, Ö., (1993) An Introduction to Bioceramics, p. 41. , in: L.L. Hench, J. Wilson (Eds.), World Scientific, Singapore; Nakamura, T., Yamamuro, T., Higashi, S., Kokubo, T., Ito, S., (1985) J. Biomed. Mater. Res., 19, p. 685; Höland, W., Vogel, W., Nauman, K., Gummel, J., (1985) J. Biomed. Mater. Res., 19, p. 303; Kasuga, T., Abe, Y., (1998) J. Mater. Res., 13, p. 1; Rawson, H., (1960) Inorganic Glass-Forming System, p. 155. , Academic, London; Abe, Y., Naruse, A., Hosoe, M., Fukui, H., Hasegawa, J., (1975) In: The 1975 Symposium on Biomaterials, p. 202. , Kyoto; Abe, Y., (1990) In: International Forum on Fine Ceramics '90, p. 78. , Nagoya; Kasuga, T., Abe, Y., (1999) J. Non-Cryst. Solids, 243, p. 70; Hosono, H., Zhang, Z., Abe, Y., (1989) J. Am. Ceram. Soc., 72, p. 1587; Posner, A.S., (1969) Phys. Rev., 49, p. 760; Kitsugi, T., Yamamuro, T., Nakamura, T., Kotani, S., Kokubo, T., Takeuchi, H., (1993) Biomaterials, 14, p. 216; Klein, C.P., De Blieck-Hogervorst, J.M., Wolke, J.G., De Groot, K., (1990) Biomaterials, 11, p. 509; Kitsugi, T., Yamamuro, T., Nakamura, T., Oka, M., (1995) Biomaterials, 16, p. 1101; Müller-Mai, C., Berger, G., Voigt, C., Bakki, B., Gross, U., (1997) Bioceramics, 10, p. 53. , in: L. Sedel, C. Rey (Eds.), Elsevier, Amsterdam; Vogel, J., Schulze, K.-J., Reif, D., Hartmann, P., Platzbecker, U., Leuner, B., (1997) Bioceramics, 10, p. 57. , in: L. Sedel, C. Rey (Eds.), Elsevier, Amsterdam; Gil, F.J., Terradas, R., Clement, J., Avila, G., Martinez, S., Planell, J.A., (1997) Bioceramics, 10, p. 553. , in: L. Sedel, C. Rey (Eds.), Elsevier, Amsterdam; Sun, K.-H., (1947) J. Am. Ceram. Soc., 30, p. 277; Arm, D.M., Tencer, A.F., Brain, S.D., Celino, D., (1996) Biomaterials, 17, p. 703; Denissen, D., Van Beck, E., Lowick, C., Papapoulos, S., Van Den Hoof, A., (1993) Bone Miner., 25, p. 123; Nguyen, T.H., Cromwell, M., Wonc, R., Beck, L.S., Plouhar, P., Onpipattatanskul, B., (1994) Proceedings of the International Symposium Control. Rel. Bioact. Mater., 21, p. 122; Uchida, A., Shinto, Y., Araki, N., Ono, K., (1992) J. Orthop. Res., 10, p. 440
Keywords: Additives; Biomaterials; Calcium Compounds; calcium phosphate; Ceramic materials; Crystal microstructure; Crystallization; Differential thermal analysis; glass; Glass ceramics; Nucleation; Phosphates; Porous materials; Precipitation (chemical); Sodium dioxide; X ray crystallography

Direct and indirect effects of P 2O 5 glass reinforced-hydroxyapatite composites on the growth and function of osteoblast-like cells - Lopes, M.A.; Knowles, J.C.; Santos, J.D.; Monteiro, F.J.; Olsen, I. (BiomaterialsBiomaterials, 2000)
Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific. Copyright (C) 2000 Elsevier Science Ltd. Human osteoblast-like cells were plated on hydroxyapatite and P 2O 5-glass reinforced hydroxyapatite composite discs. They were also cultured in the presence of media obtained by incubating the discs in the absence of cells. The effects of these direct and indirect interactions were examined by measuring cell proliferation and the expression of certain key extracellular matrix antigens. One composite was found to initially delay cell growth, while the extract of a different composite appeared to down-regulate DNA synthesis. Flow cytometry analysis showed that growth directly on the discs had little effect on collagen type I, but reduced fibronectin and osteocalcin levels. The extracts of the materials generally had less effect, although one extract obtained from the glass-reinforced hydroxyapatite significantly down-regulated fibronectin. These in vitro studies thus suggest that there were only few differences overall in the growth of the cells directly on the glass-reinforced compared with the hydroxyapatite discs and also only relatively small effects of the extracts on the cells. However, the flow cytometry results suggest that both the materials and the extracts may have a potentially important influence on connective tissue production, and that these effects are both material- and antigen-specific.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00007-7PubMed ID: 10817269Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: iolsen@eastman.ucl.ac.ukChemicals/CAS: Antigens; Biocompatible Materials; DNA, 9007-49-2; Hydroxyapatites; PhosphatesReferences: Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytoxicity in vitro (1992) Regulatory Affairs, 4, pp. 13-32;Hanson, S., Lalor, P.A., Niemi, S.M., Ratner, B.D., (1996) Biomaterials Science. An Introduction to Materials in Medicine, pp. 215-242. , B.D. Ratner, & A.S. Hoffman. Basel: Karger; Bou-Gharios, G., Osman, J., Atherton, A., Monoghan, P., Vancheeswaran, R., Black, C., Olsen, I., Expression of ectopeptidaes in scleroderma (1995) Ann Rheum Dis, 54, pp. 111-116; Goseki, T., Shimizu, N., Iwasawa, T., Takiguchi, H., Abiko, Y., Effects of in vitro cellular aging on alkaline phosphatase, cathepsin activities and collagen secretion of human periodontal ligament-derived cells (1996) Mech Age Dev, 91, pp. 1761-1783; Parkar, M.H., Kuru, L., O'Hare, M., Newman, H.N., Hughes, F., Olsen, I., Retroviral transduction of periodontal cells with a temperature-sensitive SV40 large T antigen (1999) Archs Oral Biol, 44, pp. 823-834; Simon, L.V., Beauchamp, J.R., O'Hare, M., Olsen, I., Establishment of long-term myogenic cultures from patients with Duchenne muscular dystrophy by retroviral transduction of a temperature-sensitive SV40 large T-antigen construct (1996) Exp Cell Res, 224, pp. 264-271; Clover, J., Gowen, M., Are MG-63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype (1994) Bone, 15, pp. 585-591; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Di Silvio, L., A novel application of two biomaterial for the delivery of growth hormone and its effect on osteoblasts (1995) PhD Thesis, , Univ Lon: Univ Coll Lon Med Sch; Kapuscinski, J., Skoczylas, B., Simple and rapid fluorimetric method for DNA microassay (1977) Anal Biochem, 83, pp. 252-257; Nishizawa, K., Toriyama, M., Suzuki, T., Kawamoto, Y., Yokogawa, Y., Nagae, H., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal cells (1993) J Ferm Bioengng, 75, pp. 435-437; Chesmel, K.D., Clark, C.C., Brighton, C.T., Black, J., Cellular response to chemical and morphologic aspects of biomaterial surfaces. II. The biosynthetic and migratory response of bone cell populations (1995) J Biomed Mater Res, 29, pp. 1101-1110; Harmand, M.F., Human cell culture and characterization of cell-biomaterial interface (1992) Clinical Materials, 11, pp. 145-150; Lincks, J., Boyan, B.D., Blanchard, C.R., Lohmann, C.H., Liu, Y., Cochran, D.L., Dean, D.D., Schawrtz, Z., Response of MG63 osteoblast-like cells to titanium and titanium alloy is dependent on surface roughness and composition (1998) Biomaterials, 19, pp. 2219-2232; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite composites: Secondary phases proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48, pp. 734-740; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Saramago, B., Santos, J.D., Monteiro, F.J., Hydrophobicity and zeta potencial of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res: Appl Biomater, 45, pp. 370-375; Hall, B.K., (1992) Fracture Repair and Regeneration, pp. 33-66. , Boca Raton, FL, USA: CRC Press; Legeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, , Basel: Karger; Altankov, G., Groth, T., Fibronectin matrix formation and the biocompatibility of materials (1996) J Mater Sci: Mater Med, 7, pp. 425-429; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Knowles, J.C., Hing, K., Santos, J.D., Monteiro, F.J., Olsen, I., Sedel, L., Rey, C., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1997) Bioceramics, 10, pp. 575-578. , Paris, Oxford, UK: Elsevier; Kirkpatrick, C.J., Mittermayer, C., Theoretical and practical aspects of testing potential biomaterials in vitro (1990) J Mater Sci: Mater Med, 1, pp. 9-13; Marie, P.J., De Vernejoul, M.C., Lomri, A., Stimulation of bone formation in osteoporosis patients treated with fluoride associated with increased DNA synthesis by osteoblastic cells in vitro (1992) J Bone Miner Res, 7, pp. 103-113; Davies, J.E., In vitro modelling of the bone-implant interface (1996) Anat Rec, 245, pp. 426-445; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amdee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci: Mater Med, 17, pp. 46-51; Sumner, H., Abraham, D., Bou-Gharios, G., Plater-Zyberk, C., Olsen, I., Simultaneous measurement of cell surface and intracellular antigens by multiple flow cytometry (1991) J Immun Meth, 136, pp. 259-267; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in Scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin Chim Acta, 231, pp. 69-78; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J Dent Res, 77, pp. 555-564; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of glass on the biocompatibility of plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings (1999) J Biomed Mater Res, 47, pp. 603-611
Keywords: Animal cell culture; antigen expression; Antigens; article; Biocompatibility; Biocompatible Materials; Biomaterials; Bone; Bone cells; cell antigen; Cell culture; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell structure; collagen type 1; controlled study; DNA; DNA Replication; DNA synthesis; extracellular matrix; Fibronectin; flow cytometry; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; Hydroxyapatites; immunofluorescence; In vitro; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; osteocalcin; Phosphate minerals; Phosphates; phosphorus pentoxide; priority journal; Proteins; Reinforcement; Scanning electron microscopy

Fetal heart rate baselines in twins: Interobserver agreement in antepartum estimation - Bernardes, J.; Costa-Pereira, A.; Calejo, L.; Ayres-de-Campos, D.; Patrício, B.; Pereira-Leite, L. (Journal of Reproductive Medicine for the Obstetrician and GynecologistJ. Reprod. Med. Obstet. Gynecol., 2000)
OBJECTIVE: To assess interobserver agreement in antepartum estimation of fetal heart rate (FHR) baselines in twins. STUDY DESIGN: Two residents and one specialist in obstetrics and gynecology, all with special interest in FHR monitoring, independently estimated baselines in 162 consecutive antepartum FHR tracings recorded in 24 twins. Tracings were obtained with a dual-channel fetal monitor for the simultaneous recording of both twins' heart rates. Baselines were estimated, as single values corresponding to the mean of the lowest stable FHR segment, in the absence of fetal movements and uterine contractions, within physiologic limits (110-150 beats per minute [bpm]). If these criteria were not met, the possibility of persistent bradycardia or tachycardia was considered, and if this was confirmed in a tracing with at least 40 minutes, a baseline < 110 or > 150 bpm was chosen. Interobserver agreement was assessed by the proportions of agreement (PA), kappa statistic (K) and intraclass correlation coefficient (ICCC), with 95% confidence intervals (CIs). RESULTS: Interobserver agreement was excellent, with a PA of 0.90 (95% CI: 0.89-0.91), K of 0.88 (95% CI: 0.84-0.92) and ICCC of 0.91 (95% CI: 0.88-0.94). CONCLUSION: Interobserver agreement in antepartum estimation of fetal heart rate baselines in twins was excellent with the baseline concept used in this study.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JRPMAPubMed ID: 10710739Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Depto. de Ginecologia e Obstetricia, Faculdade de Medicina do Porto, Al. Prof. Hernani Monteiro, 4200 Porto, Portugal; email: Jbernardes@mail.telepac.ptReferences: Sherman, S.J., Kovacs, B.W., Medearis, A.L., Nonstress test assessment of twins (1992) J Reprod Med, 37, pp. 804-808;Grant, J.M., The fetal heart rate is normal, isn't it?: Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Cibils, L.A., On intrapartum fetal monitoring (1996) Am J Obstet Gynecol, 174, pp. 1382-1389; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Objective computerized fetal heart rate analysis (1998) Int J Gynecol Obstet, 62, pp. 141-147; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 11, pp. 307-310; Armitage, P., Berry, G., (1994) Statistical Methods in Medical Research, pp. 273-276. , Oxford, Blackwell Science Ltd; Khan, K.S., Chien, P.F.W., Honest, M.R., Evaluating measurement variability of clinical investigations: The case of ultrasonic estimation of urinary bladder volume (1997) Br J Obstet Gynaecol, 104, pp. 1036-1043; Devoe, L.D., Carlton, E., Prescott, P., Neural network prediction of nonstress test results: How often should we perform nonstress tests? (1995) Am J Obstet Gynecol, 173, pp. 1128-1131; Bernardes, J., Ayres De Campos, D., Costa-Pereira, A., Baseline estimation in typical fetal heart rate patterns using different computerized methods (1997) Acta Obstet Gynecol Scand (Suppl), 76, p. 56;
Keywords: adult; article; clinical article; Electrocardiography; Female; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart rate variability; Heart Rate, Fetal; human; Humans; Internship and Residency; observer variation; Obstetrics; Pregnancy; Prenatal Care; priority journal; Professional Competence; Twins

Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Knowles, J.C.; Olsen, I.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells. Copyright (C) 2000 Elsevier Science Ltd. Multilayered coatings composed of mixtures of HA and P 2O 5-based bioactive glasses are of potential clinical benefit in orthopaedic and dental surgery. Pre-immersion of these materials has been reported to further enhance their efficacy in vivo, although the precise biological effects of this treatment are not yet known. In this study we have therefore prepared double-layer plasma-sprayed coatings and evaluated the effects of pre-immersion on the growth and function of human osteosarcoma cells in vitro, using the MTT assay and flow cytometry analysis, respectively. The results showed that the increase in numbers of viable cells was the same or elevated following incubation on the pre-immersed HA and glass-reinforced HA coatings compared with the non-immersed materials. In addition, the expression of bone sialoprotein and fibronectin, two key connective tissue antigens, was up-regulated in cultures grown on the pre-immersed surfaces compared with the non-treated materials. Moreover, cell numbers and antigen expression both improved as the proportion of glass increased, particularly in the pre-immersed samples. Our findings thus suggest that the immersion treatment of these materials appeared to improve the response of these bone-like cells.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00249-5PubMed ID: 10721750Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University College London, 256 Gray's Inn Road, London WC1X 8LD, United Kingdom; email: iolsen@eastman.ucl.ac.ukChemicals/CAS: Biocompatible Materials; bone sialoprotein; Coated Materials, Biocompatible; Durapatite, 1306-06-5; Fibronectins; SialoglycoproteinsManufacturers: Plasma Biotal, United KingdomReferences: Passuti, N., Daculsi, G., Martin, S., Macroporous calcium phosphate ceramics for long bone surgery in human and dogs - Clinical and histological studies (1990) Clinical Implant Materials, pp. 255-258. , V. Soltesz, & A. Lee. Amsterdam: Elsevier Science Publishers;Legeros, R., Calcium phosphate materials in restorative dentistry (1988) A Review. Adv Dent Res, 2, pp. 164-180; Hench, L.L., Bioactive ceramics: From concept to clinic (1992) J Am Ceram Soc, 74, pp. 1487-1510; Conish, H., Aoki, H., Sawai, K., (1981) Science and Medical Applications of Hydroxyaptite, , editors Tokyo: Takyama Press System Centre Co; Raemdonck, W., Ducheyne, P., Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Materials, pp. 143-166. , P. Ducheyne, & G.W. Hastings. Boca Raton, FL, USA: CRC Press; Rey, C., Freche, M., Heughebaert, M., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) Fourth Symposium on Ceramics in Medicine - Bioceramics 4, pp. 57-64. , G.W. Hastings, & K.E. Tanner. London: Butterworth-Heinemann; Nagase, M., Abe, Y., Udagwa, E., Toxicity of silica-containing calcium phosphate glasses demonstrated in mice (1992) Biomaterials, 13, pp. 172-175; Burnie, J., Gilchrist, T., Controlled released glass - A new biomaterial (1983) Ceramics in Surgery, pp. 169-176. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Burnie, F., Gilchrist, T., (1983) Ceramics in Surgery, pp. 177-180. , P. Vicenzini. Amsterdam: Elsevier Science; Rawlings, R.D., Rogers, P.S., Stokes, P.M., Glass-ceramics containing apatite (1987) High Tech Ceramics, pp. 73-82. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Santos, J.D., Lakhan, J.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Ferraz, M.P., Monteiro, F.J., Santos, J.D., In vitro bioactivity and osteocompatibility evaluation of plasma sprayed hydroxyapatite/glass composite coatings onto Ti-6Al-4V substrates (1997) Ninth International Conference on Biomedical Engineering, pp. 557-559. , In: Goh JCH, editor Singapore; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalciumphosphate, hydroxyl-apatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65; Jansen, J.A., Van Der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 4, pp. 603-610; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the bone-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci: Mater Med, 5, pp. 11-17; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., Cytotoxicity investigations of plasma-sprayed calcium-phosphate coatings (1994) J Mater Sci: Mater Med, 5, pp. 371-375; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci: Mater Med, 7, pp. 21-28; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci: Mater Med, 7, pp. 637-643; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro evaluation (1999) J Biomed Mater Res, 45, pp. 376-383; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced HA plasma sprayed coatings (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Macey, M.G., (1994) Flow Cytometry - Clinical Applications, , editor Oxford: Blackwell Scientific; Shapiro, H.M., (1995) Practical Flow Cytometry, , New York: Wiley-Liss; Melamed, M.R., Lindmo, T., Mandelsohn, M.L., (1990) Flow Cytometry and Sorting, , editors New York: Wiley-Liss; Muirhead, K.A., Horan, P.K., Applications of flow cytometry to tissue culture systems (1983) Adv Cell Culture, 3, pp. 57-91; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Pande, G., Kumar, N.A., Manogaran, P.S., Flow cytometric study of changes in intracellular free calcium during the cell cycle (1996) Cytometry, 24, pp. 55-63; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphyromonas gingivalis by a LPS specific monoclonal antibody (1994) J Periodont, 65, pp. 309-315; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of glass on the biocompatibility of plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings J Biomed Mater Res, , in press; Cowles, E.A., DeRome, M.E., Pastizzo, G., Brailey, L.L., Gronowicz, G.A., Mineralization and the expression of matrix proteins during in vivo bone development (1998) Calcif Tissue Int, 62, pp. 74-82; Globus, R.K., Dotty, S.B., Lull, J.C., Holmuhamedov, E., Humphries, M.J., Damsky, C.H., Fibronectin is a survival factor for differentiated osteoblasts (1998) J Cell Sci, 111, pp. 1385-1393; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Wojciech, G., Melamed, M.R., Darzynkiewicz, Z., Analysis of apoptosis by flow cytometry (1998) Flow Cytometry Protocols, pp. 217-238. , M.J. Jaroszeski, & R. Heller. Totowa, NJ, USA: Humana Press
Keywords: antigen expression; article; Bioactive glasses; Biocompatibility; Biocompatible Materials; Biomaterials; Cell culture; Cell Division; cell growth; cell proliferation; Cell size; Coated Materials, Biocompatible; controlled study; cytology; Cytoplasmic Granules; Dental Materials; drug manufacture; Durapatite; Fibronectin; Fibronectins; flow cytometry; Flow cytometry analysis; glass; Glass fibers; Glass-reinforced hydroxyapatite; Growth kinetics; human; human cell; Humans; hydroxyapatite; in vitro study; materials testing; orthopedics; Osteosarcoma; osteosarcoma cell; Phosphates; Plasma spraying; Pre-immersion; priority journal; protein expression; Proteins; Sialoglycoproteins; sialoprotein; Sprayed coatings; Surface Properties; technique; Tumor Cells, Cultured

Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications - Lopes, M.A.; Silva, R.F.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
P 2O 5 glass reinforced hydroxyapatite composite materials were prepared through a liquid-phase sintering process. Secondary phases, β- and α- tricalcium phosphate (β-TCP and α-TCP), were formed in the microstructure of the composites, due to the reaction between the liquid glassy phase and the hydroxyapatite matrix. The dynamic Young's modulus (E) and shear modulus (G) of these composites were determined using an impulse excitation method. By applying the Duckworth-Knudsen equation, the elastic property results were correlated with the relative proportion of β-TCP and α-TCP phases and with the porosity percentage present in the microstructure. Glass reinforced hydroxyapatite composites showed lower Young's and shear moduli than unmodified hydroxyapatite, mainly due to presence of β-TCP phase. The Duckworth-Knudsen model demonstrated an exponential dependence of E and G modulus with porosity and mathematical equations were derived for composite materials with porosity correction factors (b) of 4.04 and 4.11, respectively, indicating that porosity largely decreased both E and G moduli. (C) 2000 Elsevier Science Ltd. 2O 5 glass reinforced hydroxyapatite composite materials were prepared through a liquid-phase sintering process. Secondary phases, β- and α-tricalcium phosphates (β-TCP and α-TCP), were formed in the microstructure of the composites, due to the reaction between the liquid glassy phase and the hydroxyapatite matrix. The dynamic Young's modulus (E) and shear modulus (G) of these composites were determined using an impulse excitation method. By applying the Duckworth-Knudsen equation, the elastic property results were correlated with the relative proportion of β-TCP and α-TCP phases and with the porosity percentage present in the microstructure. Glass reinforced hydroxyapatite composites showed lower Young's and shear moduli than unmodified hydroxyapatite, mainly due to the presence of β-TCP phase. The Duckworth-Knudsen model demonstrated an exponential dependence of E and G modulus with porosity and mathematical equations were derived for composite materials with porosity correction factors (b) of 4.04 and 4.11, respectively, indicating that porosity largely decreased both E and G moduli.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00248-3PubMed ID: 10711972Language of Original Document: EnglishCorrespondence Address: Lopes, M.A.; INEB Inst. de Engenharia Biomedica, Laboratorio de Biomaterials, Rua do Campo Alegre 823, 4150 Porto, PortugalChemicals/CAS: Biocompatible Materials; Hydroxyapatites; PhosphatesReferences: Burstein, A., Wright, T.M., (1994) Fundamentals of Orthopaedic Biomechanics, , Lippincott: Williams & Wilkins;Carter, D.R., Giori, N.J., Effect of mechanical stresses on tissue differentiation in the bony implant bed (1991) In the Bone-material Interface, pp. 367-379. , J.E. Davies. Toronto: University of Toronto Press; (1995) E - Advanced Technical Ceramics, (PART 2). , European prestandard, ref. no. ENV 843-2:; Schreiber, E., Anderson, O.L., Soga, N., (1989) Elastic Constant and Their Measurements, , New York: McGraw-Hill; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Knowles, J.C., Talal, S., Santos, J.D., Sintering effects in a glass reinforced hydroxyapatite (1996) Biomaterials, 17, pp. 1437-1442; Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1998) Bioceramics, 10, pp. 575-578; Rice, R.W., Microstructure dependence of mechanical behaviour (1977) Treatise on Materials Science and Technology, 11, pp. 200-382. , MacCrone R.K. New York: Academic Press; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Murtage, B., (1981) Advanced Linear Programming, , New York: McGraw-Hill; Chátal, V., (1990) Linear Programming, , New York: W. H. Freeman; Tampieri, A., Celotti, G., Szontagh, F., Landi, E., Sintering and characterisation of hydroxyapatite and tricalcium phosphates with control of their strength and phase porosity (1997) J Mater Sci, 8, pp. 29-37; Knowles, J.K., Development of hydroxyapatite with enhanced mechanical properties: Effect of high glass additions on mechanical properties and phase stability of sintered hydroxyapatite (1994) Br Ceram Trans, 93, pp. 100-103; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Science. Tokyo: Takayama Press System Center Co. Inc; Sax, M., Zografou, C., Telle, R., Kalawrytimos, G., Properties of sintered apatite ceramics (1995) Ceramic Processing Science and Technology, Ceramic Transactions, 51, pp. 701-705. , In: Hausner H, editor; Katz, J.L., Akers, A.S., Germiller, J.A., Obremski, S.M., Singh, S., The elastic properties of apatites and tricalcium phosphates-calcite mixtures (1989) Bioceramics, 1, pp. 86-91; Dewith, G., Vandijk, J.A., Hattu, N., Prijs, K., Preparation, microstructure and mechanical properties of dense polycrystalline hydroxyapatite (1981) J Mater Sci, 16, pp. 1592-1598; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812
Keywords: article; Biocompatible Materials; Ceramic matrix composites; Chemical analysis; chemical composition; composite graft; Duckworth-Knudsen model; Elastic moduli; Elasticity; glass; hydroxyapatite; Hydroxyapatite glass composites; Hydroxyapatites; Implants (surgical); Mathematical models; Microstructure; Molecular Structure; Phosphate minerals; Phosphates; porosity; priority journal; Shear modulus; shear stress; young modulus; Young's modulus

Object recognition in image sequences with cellular neural networks - Milanova, M.; Büker, U. (NeurocomputingNeurocomputing, 2000)
In this paper, the application of CNN associative memories for 3D object recognition is presented. The main idea is to analyse the optical flow in an image sequence of an object. Several features of the optical flow between two succeeding images are calculated and merged to a time series of features for the whole image sequence. These features show several object specific characteristics and are used for a classification step in an object recognition system. Therefore, the feature vectors of an object set are learnt and recalled by an associative memory based on the paradigm of cellular neural networks (CNN). (C) 2000 Elsevier Science B.V.In this paper, the application of CNN associative memories for 3D object recognition is presented. The main idea is to analyze the optical flow in an image sequence of an object. Several features of the optical flow between two succeeding images are calculated and merged to a time series of features for the whole image sequence. These features show several object specific characteristics and are used for a classification step in an object recognition system. Therefore, the feature vectors of an object set are learnt and recalled by an associative memory based on the paradigm of cellular neural networks (CNN).
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: NRCGEdoi: 10.1016/S0925-2312(99)00177-0Language of Original Document: EnglishCorrespondence Address: Buker, U.; Heinz Nixdorf Institute, University of Paderborn, Department of Electrical Engineering, 33095 Paderborn, Germany; email: bueker@get.uni-paderborn.deReferences: Bradski, G., Grossberg, S., Fast-learning VIEWNET architectures for recognizing three-dimensional objects from multiple two-dimensional views (1995) Neural Networks, 8 (7-8), pp. 1053-1080;Büker, U., Hartmann, G., Knowledge based view control of a neural 3D object recognition system (1996) In: Proceedings of the 13th International Conference on Pattern Recognition, ICPR'96, Wien, 4, pp. 24-29. , IEEE Computer Soc. Press, Los Alamitos; Büker, U., Hybrid object models: combining symbolic and subsymbolic object recognition strategies (1998) In: Proceedings of the 4th International Conference on Information Systems, Analysis, and Synthesis, 1, pp. 444-451. , IIIS, Orlando; Bülthoff, H., Little, J., Poggio, T., A parallel algorithm for real-time computation of optical flow (1989) Nature, 337, pp. 549-553; Bülthoff, H., Edelman, S., Tarr, M., How are three-dimensional objects represented in the brain? (1994) Technical Report, A.I.Memo N1479, , Massachusetts Institute of Technology, A.I. Lab; Chua, L.O., Yang, L., Cellular neural networks: Theory (1988) IEEE Trans. Circuits Systems, 35, pp. 1257-1272; Chua, L.O., Roska, T., The CNN Paradigm (1993) IEEE Trans. Circuits Systems (Part I) CAS-40, 3, pp. 559-577; Fu, L.M., Analysis of the dimensionality of neural networks for pattern recognition (1990) Pattern Recognition, 23, pp. 1131-1140; Grassi, G., A new approach to design cellular neural networks for associative memories (1997) IEEE Trans. Circuits Systems - I Fundam. Theory Appl., 44 (9), pp. 362-366; Hartmann, G., Drüe, S., Dunker, J., Kräuter, K.O., Mertsching, B., Seidenberg, E., The SENROB Vision-System and its Philosophy (1994) In: Proceedings of the 12th International Conference on Pattern Recognition ICPR'94, 2, pp. 573-576. , Jerusalem, IEEE Computer Soci. Press, Los Alamitos; Hartmann, G., Büker, U., Drüe, S., A hybrid neuro-artificial intelligence architecture (1999) Handbook on Computer Vision and Applications, 3, pp. 153-196. , in: B. Jähne et al. (Eds.), Academic Press, San Diego; Hebert, M., (1995) Object Recognition in Computer Vision, , (Eds.), Springer, New York; Kikuchi, M., Fukushima, K., Neural network model of the visual system: Binding: Form and motion (1996) Neural Networks, 9 (8), pp. 1417-1427; Kosslyn, S.M., (1995) Image and Brain, , Cambridge: MIT Press; Lin, W.G., Wang, S.S., A new neural model for invariant pattern recognition (1996) Neural Networks, 9 (5), pp. 899-913; Little, J., Boyd, J., Describing motion for recognition (1995) IEEE Symp. Comput. Vision, pp. 235-240; Little, J., Boyd, J., (1997) Recognizing People by their Gait: The Shape of Motion, , http://www-vision.ucsd.edu/, On-line document; Liu, D., Michel, A., Sparsely interconnected neural networks for associative memories with applications to cellular neural networks (1994) IEEE Trans. Circuits Systems - II Analog Digital Signal Process, 41 (4), pp. 295-307; Liu, D., Cloning template design of cellular neural networks for associative memories (1997) IEEE Trans. Circuits Systems - I Fundam. Theory Appl., 44 (7), pp. 646-650; Liu, D., Lu, Z., A new synthesis approach for feedback neural networks based on the perceptron training algorithm (1997) IEEE Trans. Neural Networks, 8 (6), pp. 1468-1482; Michel, A., Jie Si, Yen, G., Analysis and Synthesis of a Class of Discrete-Time Neural Networks Described on Hypercubes (1991) IEEE Trans. Neural Networks, 2 (1), pp. 32-46; Pandya, A., MacY, R., (1996) Pattern Recognition with Neural Networks in C++, , CRC Press, Florida; Rekecsky, C., Roska, T., Ushida, A., CNN-based difference-controlled adaptive non-linear image filters (1998) Internat. J. of Circuit Theory Appl., 26 (4), pp. 374-423; Roska, T., Vandewalle, J., (1993) Cellular Neural Networks, , John Wiley & Sons, New York; Szolgay, P., Szatmari, I., Laszlo, K., A Fast Fixed Point Learning Method to Implement Associative Memory on CNN's (1997) IEEE Trans. Circuits Systems-I: Fundamental Theory and Applications, 44 (4), pp. 362-366; Treisman, A., A feature-integration theory of attention (1980) Cognitive Psychology, 12, pp. 97-136; Tn, S., Hao, J., Vanderwalle, J., Cellular neural networks as a model of associative memories (1990) Proceedings of the CNNA-90, pp. 26-35. , Budapest, IEEE, New York
Keywords: algorithm; artificial neural network; Associative memory; Associative storage; Cellular neural networks; Computational methods; computer system; Image analysis; Image sequences; mathematical computing; Object recognition; Optical flow; Optical flows; Pattern recognition; Pattern recognition systems; priority journal; review; Three dimensional computer graphics; Time series analysis; Vectors

Remote foetal heart rate acquisition and analysis - Marques, P.; Marques de Sa, J.P.; Bernardes, J.; Sousa, P. (Computers in CardiologyComput Cardiol, 2000)
The remote foetal monitoring and analysis is part of INTERCARE project - an integrated healthcare system applied to Electrocardiography and Cardiotocography. Its aim is to provide low cost and wide spread technological infrastructure that supports an integrated healthcare system to users and healthcare providers. This paper illustrates the work done in the cardiotocography area. We have developed a system for remote acquisition and analysis of FHR. The system uses a portable 'foetal detector' which can be used by the pregnant woman to acquire the heart beats. This detector sends a modulated audio signal via the telephone line or a computer connected to Internet. At the processing end the signal received by the telephone can be switched to the computer sound acquisition board. The signal is then processed by an application that reads from the soundcard. Due to the noise added by devices and telephone lines, the signal is filtered using optimal FIR filters and is decimated until its band of interest covers the peaks of the heart sounds. Next the signal is processed by a specially developed adaptive correlation algorithm in order to obtain the heart beat instants. The whole process operates in real time. The adaptive correlation algorithm performs a continuous adjustment of the heart beat template and threshold detection levels.
Conference code: 45063Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: COCADLanguage of Original Document: EnglishCorrespondence Address: Marques, P.; INEB - Instituto de Engenharia, Biomedica, Porto, Portugal
Keywords: Adaptive algorithms; Adaptive correlation algorithm; Cardiology; Cardiotocography; Client server computer systems; Data acquisition; Data warehouse; Database systems; Electrocardiography; FIR filters; Foetal heart rate; Internet; Patient monitoring; Remote foetal monitoring; Signal filtering and prediction; Sonoscope; Spurious signal noise; Telephone

Self-assembly and surface structure of an amphiphilic graft copolymer, polystyrene-graft-ω-stearyl-poly(ethylene oxide) - Ji, J.; Feng, L.; Qiu, Y.; Yu, X.; Barbosa, M.A. (Journal of Colloid and Interface ScienceJ. Colloid Interface Sci., 2000)
Surface properties of the polystyrene-graft-ω-stearyl-poly(ethylene oxide) (PS-g-SPEO) have been characterized by X-ray photoelectron spectroscopy (XPS), differential scanning calorimetry (DSC), contact angle, and spin probe techniques. The XPS results indicate that the surface and bulk composition of the PS-g-SPEO copolymers differ remarkably from each other. The stearyl and EO components enrich at the copolymer/air interfaces due to the self-assembly of the stearyl groups. At the PS-g-SPEO-72.6 surface (the x in PS-g-SPEO-x indicates the bulk density of the SPEO in wt%), the self- assembly of the hydrophobic stearyl groups is strong enough to form a stable liquid crystalline phase as indicated by DSC. At polymer/water interfaces, PS-g-SPEO-72.6 presents a hydrophilic surface with low PEO mobility, whereas PS-g-SPEO-50.6 and PS-g-SPEO-31.0 present the hydrophobic surface with high PEO mobility. The two different types of the surfaces, with different characters in surface energy, surface mobility of PEO, and surface architecture of SPEO, will be quite valuable as models for detecting the synergistic action of the PEO chains and the stearyl groups (specific ligand for albumin binding) in protein solutions. (C) 2000 Academic Press.
Cited By (since 1996): 12Export Date: 21 November 2012Source: ScopusCODEN: JCISAdoi: 10.1006/jcis.2000.6729Language of Original Document: EnglishCorrespondence Address: Ji, J.; Instituto de Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jian@ibmc.up.ptChemicals/CAS: macrogol, 25322-68-3; polystyrene, 9003-53-6; stearic acid, 57-11-4, 646-29-7References: Brash, J.L., (1983) Biocompatible Polymer, Metals and Composites, p. 35. , M. Szycher. Lancaster: Technomic;Gombotz, W.R., Guanghui, W., Horbett, T.A., Hoffman, A.S., (1991) J. Biomed. Mater. Res., 25, p. 1547; Munro, M.S., Quattrone, A.J., Ellsworth, S.R., Kulkarni, P., Eberhart, R.C., (1981) Trans. ASAIO, 17, p. 499; Grasel, T.G., Pierce, J.A., Cooper, S.L., (1987) J. Biomed. Mater. Sci., 21, p. 815; Duncan, A.C., Sefton, M.V., Brash, J.L., (1997) Biomaterials, 18, p. 1585; Keogh, J.R., Velander, F.F., Eaton, W., (1992) J. Biomed. Mater. Sci., 26, p. 441; Lee, J.H., Jeong, B.J., Lee, H.B., (1997) J. Biomed. Mater. Sci., 34, p. 105; Bots, J.G.F., Van Der Does, L., Bentjes, A., (1986) Biomaterials, 7, p. 393; Osterberg, E., Holmberg, K., Schuman, T.P., Riggs, J.A., Burns, N.L., Van Alstine, J.M., Harris, J.M., (1995) J. Biomed. Mater. Res., 29, p. 741; Hubbell, J.A., (1997) Polym. Prepr., 38, p. 528; Harris, J.M., (1997) Polym. Prepr., 38, p. 520; Qiu, Y.X., Yu, X.J., Feng, L.X., (1992) Markromol. Chem., 173, p. 1377; Neumann, A.W., Good, R.J., (1979) Surface and Colloid Science, Vol. 11, Experimental Methods, p. 31. , R. J. Good, & R. R. Stromberg. New York: Plenum Press; Ji, J., Feng, L., Qiu, Y., Yu, X., (1998) Macromol. Rapid Commun., 19, p. 473; Cameron, G.G., (1989) Comprehensive Polymer Science, Polymer Characterization, p. 517. , S. G. Allen. Oxford: Pergamon Press; Andrade, J.D., Ma., S.M., (1979) J. Colloid Interface Sci., 12, p. 488; Ranter, B.D., (1985) Surface and Interfacial Aspects of Biomedical Polymers Vol.1, p. 374. , J. D. Andrade. New York: Plenum Press; Takahara, A., Jo, N.J., Kajiyama, T., (1989) J. Biomater. Sci. Polym. Ed., 1, p. 17; Lide, D.R., (1996) Handbook of Chemistry and Physics, , D. R. Lider. Boca Raton: CRC Press; Van Oss, C.J., (1994) Interfacial Forces in Aqueous Media, pp. 170-177. , C. J. Van Oss. New York: Marcel Dekker Inc; Gombotz, W.R., Guanhui, W., Horebett, T.A., Hoffman, A.S., (1992) Poly(ethylene Glycol) Chemistry: Biotechnical and Biomedical Application, pp. 247-261. , J. M. Harris. New York: Plenum Press; Wu, D., Jian, K., (1995) Sci. China (B), 25, p. 1121; Wu, D., Jian, K., (1995) Sci. China (B), 26, p. 409; Ji, J., Feng, L., Qiu, Y., Yu, X., Polymer, , in press; Hester, J.F., Banerjee, P., Mayes, A.M., (1999) Macromolecules, 32, p. 1643
Keywords: Amphiphilic copolymer; article; biomaterial; copolymer; crystal; differential scanning calorimetry; electron microscopy; electron spin resonance; hydrophobicity; macrogol; polystyrene; priority journal; protein assembly; protein binding; protein structure; Self-assembly; stearic acid; Surface structure; X ray analysis

Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement - Lopes, M.A.; Knowles, J.C.; Santos, J.D. (BiomaterialsBiomaterials, 2000)
Phase transformations and interstitial and/or substitution of trace elements during the liquid-phase sintering process of P 2O 5-CaO-MgO glass-reinforced hydroxyapatite (GR-HA) composites were examined by X-ray diffraction and Rietveld analyses. Using the Rietveld method for structure refinement, changes in the lattice parameters of the two main phases of the composites, hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), as well as changes in several bond lengths and in the occupancy of the hydroxyl oxygen site in the HA phase structure were assessed. The glasses gave rise to formation of between approximately 45 and 50% of β-TCP, with evidence for the Mg 2+ enhancing the formation of β-TCP. Between 1300 and 1350°C, the β-TCP inverts to α-TCP, without further decomposition of the residual HA. The glasses showed evidence for stabilisation of the hydroxyl group located in the hydroxyl channels. This is supported by measurements of the hydroxyl channel radius (R(c)), the Ca 2-OH bond length and the hydroxyl oxygen occupancy (O(occ)). Results showed that the Mg 2+ containing glasses induced the β-TCP phase formation in the structure of GR-HA composites and retarded the β-TCP into α-TCP transformation at higher temperatures. The chemical composition of the P 2O 5 glasses also induces modifications in the lattice parameters of the crystallographic phases present in the microstructure of the composites. This suggests some substitution of Mg 2+-for-Ca 2+ in the β-TCP structure during the liquid-phase sintering process. Copyright (C) 2000 Elsevier Science Ltd. Phase transformations and interstitial and/or substitution of trace elements during the liquid-phase sintering process of P 2O 5-CaO-MgO glass-reinforced hydroxyapatite (GR-HA) composites were examined by X-ray diffraction and Rietveld analyses. Using the Rietveld method for structure refinement, changes in the lattice parameters of the two main phases of the composites, hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), as well as changes in several bond lengths and in the occupancy of the hydroxyl oxygen site in the HA phase structure were assessed. The glasses gave rise to formation of between approximately 45 and 50% of β-TCP, with evidence for the Mg 2+ enhancing the formation of β-TCP. Between 1300 and 1350 °C, the β-TCP inverts to α-TCP, without further decomposition of the residual HA. The glasses showed evidence for stabilization of the hydroxyl group located in the hydroxyl channels. This is supported by measurements of the hydroxyl channel radius (R c), the Ca 2-OH bond length and the hydroxyl oxygen occupancy (O occ). Results showed that the Mg 2+ containing glasses induced the β-TCP phase formation in the structure of GR-HA composites and retarded the β-TCP into α-TCP transformation at higher temperatures. The chemical composition of the P 2O 5 glasses also induces modifications in the lattice parameters of the crystallographic phases present in the microstructure of the composites. This suggests some substitution of Mg 2+-for-Ca 2+ in the β-TCP structure during the liquid-phase sintering process.
Cited By (since 1996): 14Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(00)00068-5PubMed ID: 10919694Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: jdsantos@alf.fe.up.ptChemicals/CAS: beta-tricalcium phosphate; Biocompatible Materials; Calcium Phosphates; Hydroxyapatites; Magnesium, 7439-95-4; Trace Elements; tricalcium phosphate, 7758-87-4References: Elliot, J.C., Structure and chemistry of the apatites and other calcium orthophosphates (1994) Studies in Inorganic Chemistry, 18. , Amsterdam: Elsevier Science;Okazaki, M., Sato, M., Computer graphics of hydroxyapatite and β -tricalcium phosphate (1990) Biomaterials, 11, pp. 573-578; Hench, L.L., Wilson, J., An introduction to bioceramics (1993) Advanced Series in Ceramics, 1, pp. 139-180. , editors. Singapore: World Scientific; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15 (1), pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Lopes, M.A., Santos, J.D., Monteiro, F.J., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Li, P., (1993) In Vitro and in Vivo Calcium Phosphate Induction on Gel Oxides, , PhD thesis, Leiden, Offsetdrukkerij Haveka B.V. ed; Hagen, A.R., Structural features of biologically involved phosphates (1970) Acta Odontol Scand, 58, pp. 149-173; Narasaraju, T.S.B., Phebe, D.E., Review: Some physicochemical aspects of hydroxylapatite (1996) J Mater Sci, 31, pp. 1-21; Kay, M.I., Young, R.A., Posner, A.S., The crystal structure of hydroxyapatite (1964) Nature, 204, pp. 1050-1052; Montel, G., Bonel, G., Heughebaert, J.C., Trombe, J.C., Rey, C., New concepts in the composition, crystallisation and growth of the mineral component of calcified tissues (1981) J Crystal Growth, 53, pp. 74-99; Fanovich, M.A., Castro, M.S., Porto López, J.M., Analysis of the microstructural evolution in hydroxyapatite ceramics by electrical characterisation (1999) Ceramics Int, 25, pp. 517-522; Bigi, A., Falini, G., Foresti, E., Gazzano, M., Ripamonti, A., Roveri, N., Rietveld structure refinements of calcium hydroxyapatite containing magnesium (1996) Acta Crystallogr, 52, pp. 87-92; Okazaki, M., Sato, M., Takahashi, J., Space-cutting model of hydroxyapatite (1995) Biomaterials, 16, pp. 45-49; Ravalgloli, A., Krajewski, A., (1992) Bioceramics, pp. 16-59. , London: Chapman & Hall; Okazaki, M., Takahashi, J., Kimura, H., Unstable behavior of magnesium-containing hydroxyapatites (1986) Caries Res, 20, pp. 324-331; Kotani, S., Fijita, Y., Kitsugi, T., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bone bonding mechanism of β -tricalcium phosphate (1991) J Biomed Mater Res, 25, pp. 1303-1315; Eanes, E.D., Thermochemical studies on amorphous calcium phosphate (1970) Calcif Tiss Res, 5, pp. 133-145; De Groot, K., Klien, P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., Chemistry of calcium phosphate bioceramics (1990) Handbook of Bioactive Ceramics, 2, pp. 3-16. , T. Yamamuro, L.L. Hench, Wilson J. Boca Raton, FL: CRC Press; Legeros, R.Z., Calcium phosphates in oral biology and medicine (1991) Monographs in Oral Science, 15, pp. 87-107. , New York: Karger
Keywords: article; Biocompatible Materials; Biomedical engineering; Calcium Compounds; calcium phosphate; Calcium phosphates; Chemical bonds; chemical composition; Composition effects; Crystal lattices; Crystal microstructure; crystal structure; Crystallization; decomposition; Fiber reinforced materials; glass; Glass fibers; Glass-reinforced hydroxyapatite; Glass-reinforced hydroxyapatite composites; hydroxyapatite; Hydroxyapatites; Implants (surgical); Liquid-phase sintering; Magnesium; Mg-apatites; Models, Molecular; phase transition; Phase transitions; Phosphate minerals; priority journal; Rietveld refinement; Rietveld refinement analysis; Sintering; spectacles; structure analysis; temperature; Thermodynamics; Trace Elements; Tricalcium phosphate; X ray analysis; X ray crystallography; β-TCP

CaO-P 2O 5 glass hydroxyapatite double-layer plasma-sprayed coating: In vitro bioactivity evaluation - Ferraz, M.P.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Double-layer composite coatings composed of a P 2O 5-based glass/Ca 10(PO 4) 6(OH) 2 (HA) mixture top layer and a simple HA underlayer, on Ti-6AI-4V substrates, were prepared using a plasma-spraying technique. The in vitro bioactivity of these coatings was assessed by immersion testing in simulated body fluid. Both scanning electron microscopy (SEM) analysis and the ionic solution changes followed by atomic absorption spectroscopy and the molybdenum blue method demonstrated that these composite coatings induce a faster surface Ca-P layer formation than the simple HA coatings used as a control. X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the Ca-P layer formed was apatite. The combination of SEM and XPS analyses showed that the apatite layer was a calcium-deficient hydroxyapatite with a Ca/P ranging from 1.3 to 1.4 with CO 3 2- groups contained in the structure. Double-layer composite coatings composed of a P 2O 5-based glass/Ca 10(PO 4) 6(OH) 2 (HA) mixture top layer and a simple HA underlayer, on Ti-6AI-4V substrates, were prepared using a plasma-spraying technique. The in vitro bioactivity of these coatings was assessed by immersion testing in simulated body fluid. Both scanning electron microscopy (SEM) analysis and the ionic solution changes followed by atomic absorption spectroscopy and the molybdenum blue method demonstrated that these composite coatings induce a faster surface Ca-P layer formation than the simple HA coatings used as a control. X-ray photoelectron spectroscopy (XPS) analysis demonstrated that the Ca-P layer formed was apatite. The combination of SEM and XPS analyses showed that the apatite layer was a calcium-deficient hydroxyapatite with a Ca/P ranging from 1.3 to 1.4 with CO 3 2- groups contained in the structure.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19990615)45:4<376::AID-JBM13>3.0.CO;2-SLanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Departamento Engenharia Metalurgica, FEUP, Universidade do Porto, R. dos Bragas, 4099 Porto Codex, PortugalChemicals/CAS: Alloys; Calcium, 7440-70-2; CaO-SiO2-P2O5-CaF2 glass; Coated Materials, Biocompatible; Durapatite, 1306-06-5; Phosphates; Powders; Resin Cements; Solutions; titanium alloy (TiAl6V4), 12743-70-3; Titanium, 7440-32-6References: Denissen, H., Mangano, C., Venini, G., (1985) Hydroxylapatite Implants., , Padua: Piccin Nuova Libraria, S.P.A;Van Raemdonck, W., Ducheyne, P., De Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Biomaterials, pp. 143-166. , Ducheyne P, Hastings GW, editors, Boca Raton, FL: CRC Press; Legeros, R.Z., Incorporation of magnesium in synthetic and biological apatites (1994) Tooth Enamel IV., pp. 32-36. , Fearnead RW, editor. Amsterdam: Elsevier Science; Jha, L.J., Best, S.M., Knowles, J.C., Rehman, I., Santos, J.D., Bonfield, W., Preparation and characterization of fluoride-substituted apatites (1997) J Mater Sci Mater Med, 8, pp. 185-191; Geesink, R.G.T., Degroot, K., Chemical implant fixation using hydroxyl-apatite coatings (1987) Clin Orthop, 2, pp. 147-170; Radin, S., Ducheyne, P., The effect of plasma sprayed induced changes in the characteristics on the in vitro stability of calcium phosphate ceramics (1990) Transactions of the 16th Annual Meeting of the Society for Biomaterials XIII, pp. 128-130; Cook, S.D., Thomas, K.A., Hydroxyapatite coated porous titanium for use as an orthopaedic biologic attachment (1989) Clin Orthop, 230, pp. 303-312; McPherson, R., Gane, N., Bastow, T.J., Structural characterization of plasma-sprayed hydroxylapatite coatings (1995) J Mater Sci Mater Med, 6, pp. 327-334; De Groot, K., Geesink, R., Klein, C.P.A.T., Serekian, P., Plasma sprayed coatings of hydroxylapatite (1987) J Biomed Mater Res, 21, pp. 1375-1381; Ravagliolli, A., Krajewszki, A., Laudadio, P., Presutti, L., Cunsolo, E., Martinetti, R., About ceramics for stapedial prostheses and the ossicular chain (1992) Fifth International Symposium on Ceramics in Medicine-Bioceramics 5, pp. 451-458. , Yamamuro T, Kokubo T, Nakamura T, editors. Kyoto: Kobunshi Kankokai; Hastings, G.W., Daily, D., Hydroxyapatite coatings (1989) First International Symposium on Ceramics in Medicine-Bioceramics 1, pp. 355-358. , Oonishi H, Aoki H, Sawai K, editors. Tokyo: Ishiyaku EuroAmerica; Aoki, H., Medical applications of hydroxyapatite (1991) Science and Medical Applications of Hydroxyaptite, pp. 175-192. , Aoki H, Sawai K, editors. Tokyo: Takyama Press System Centre; Rey, C., Calcium phosphate biomaterials and bone mineral: Differences in composition, structures and properties (1990) Biomaterials, 11, pp. 13-15; Evans, G., Behiri, J., Currey J, B.W., Microhardness and young's modulus in cortical bone exhibiting a wide range of mineral volume fractions, and in a bone analogue (1990) J Mater Sci Mater Med, 1, pp. 38-43; Rey, C., Froche, M., Heughebaert, M., Heughebaert, J.C., Lacout, J.L., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) Fourth International Symposium on Ceramics in Medicine-Bioceramics 4, pp. 57-60. , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; Knowles, J.C., Talal, S., Santos, J.D., Sintering effects in a glass reinforced hydroxyapatite (1996) Biomaterials, 17, pp. 1437-1442; Kokubo, T., Hayashi, T., Sakka, S., Kitsugi, T., Yamamuro, T., Takagi, M., Shibuya, T., Surface structure of a load bearable bioactive glass-ceramic A-W (1981) High Tech Ceramics, pp. 175-184. , Vicenzini P, editor. Amsterdam: Elsevier Science Publisher BV; Hench, L., Anderson, O.H., LaTorre, G.P., The kinetics of bioactive ceramics. Part III: Surface reactions for bioactive glasses compared with inactive glass (1991) Fourth International Symposium on Ceramics in Medicine-Bioceramics 4, , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; 155-162; Daculsi, G., LeGeros, R.Z., Heughebart, M., Barbieux, I., Formation of a carbonate apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46, pp. 20-27; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Kitsugi, T., Yamamuro, T., Ca-P rich layer formed on high strength bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Ducheyne, P., Radin, S., Ishikawa, K., Kim, C.S., Dissolution and precipitation of calcium phosphate phases on biomaterials correlates with in vivo bioactivity (1991) Fourth International Symposium on Ceramics in Medicine-Bioceramics 4, pp. 135-144. , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; Rey, C., Hina, A., Amrah-Bouali, S., Ranz, X., Surface reactions of calcium-phosphate bioceramics, comparison with bone mineral surface chemistry (1995) Fourth Euro Ceramics., 8, pp. 301-312. , Ravaglioli A, editor. Faenza: Gruppo Editoriale Faenza Editrice; Van Blitterswijk, C.A., Grote, J.J., Kuypers, W., Blok-Van Hoek, C.J.G., Daems, W.T., Bioreactions at the tissue/hydroxyapatite interface (1985) Biomaterials, 6, pp. 243-251; Ducheyne, P., Bioceramics: Material characteristics versus in vivo behavior (1987) J Biomed Mater Res, 21, pp. 219-236; Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Nakamura, T., Kitsogi, T., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J Biomed Mater Res, 24, pp. 471-488; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites (1995) J Mater Sci Mater Med, 6, pp. 348-352; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., Apatite coated on organic polymers by biomimetic process: Improvement in adhesion to substrate by HC1 treatment (1995) J Mater Sci Mater Med, 6, pp. 319-326; Neo, M., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bando, Y., A comparative study of ultrastructures of the interfaces between four kinds of surface-active ceramic and bone (1992) J Biomed Mater Res, 26, pp. 1419-1432; Li, P., Ohtsuki, C., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., Process of formation of bone-like apatite layer on silica gel (1993) J Mater Sci Mater Med, 4, pp. 127-131; Santos, J.D., Jha, L.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Neo, M., Kotani, S., Fujita, Y., Yamamuro, T., Bando, Y., Ohtsuki, C., Kokubo, T., Differences in ceramic-bone interface between surface-active ceramics and resorbable ceramics: A study by scanning and transmission electron microscope (1992) J Biomed Mater Res, 26, pp. 255-267; Li, P., Yang, Q., Zhang, F., Kokubo, T., The effect of residual glassy phase in a bioactive glass-ceramic on the formation of its surface apatite layer in vitro (1992) J Mater Sci Mater Med, 3, pp. 452-456; Kotani, S., Fujita, Y., Kitsugi, T., Nakamura, T., Yamamuro, T., Bone bonding mechanism of β-tricalcium phosphate (1991) J Biomed Mater Res, 25, pp. 1303-1315; Daculsi, G., LeGeros Rz, H.M., Barbieux, I., Formation of carbonate-apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46, pp. 20-27; Silva, P.L., Monteiro, F.J., Santos, J.D., Knowles, J.C., Adhesion and microstructural characterisation of plasma sprayed hydroxyapatite-glass ceramic coatings onto Ti-6Al-4V substrates (1998) Surf Coatings Technol, 102, pp. 191-196; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Yamamuro, T., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J Biomed Mater Res, 3, pp. 79-83; Blakeslee, D.M., Dal-Favero, M.E., (1997) NIST X-ray Photoelectron Spectroscopy Database, , Gaitherburg, MD: National Institute of Standards and Technology; Anderson, O.H., Kangasniemi, I., Calcium phosphate formation at the surface of bioactive glass in vitro (1991) J Biomed Mater Res, 25, pp. 1019-1030; Santos, J.D., Jha, L.J., Monteiro, F.J., In vitro calcium phosphate formation on SiO 2-Na 2O-CaO-P 2O 5 glass reinforced hydroxyapatite composite: A study by XPS analysis (1996) J Mater Sci Mater Med, 7, pp. 181-185; Verhoeven, J.A.T., Van Doveren, H., An XPS investigation of the interface of methane, ethyne, ethene and ethane with barium surface (1982) Surf Sci, 123, pp. 369-383
Keywords: alloy; Alloys; Apatite; article; Atomic absorption spectroscopy; Atomic spectroscopy; Bioactivity; Biocompatibility; biomaterial; Biomaterials; Biomedical engineering; Body fluids; Calcium; Calcium Compounds; CaO SiO2 P2O5 CaF2 glass; CaO-SiO2-P2O5-CaF2 glass; Chemical analysis; chemical composition; Coated Materials, Biocompatible; Double layer coatings; Double-layer coatings; Durapatite; film; glass; Glass plasma spraying; human; Humans; hydroxyapatite; immersion; implant; in vitro study; Ionic solution changes; Magnesium; materials testing; Molybdenum blue; Multilayers; Particle Size; phosphate; Phosphate minerals; Phosphates; Phosphorus Compounds; phosphorus pentoxide; Plasma spraying; potassium; powder; Powders; resin cement; Resin Cements; Scanning electron microscopy; Sodium; solution and solubility; Solutions; structure analysis; Substrates; Surface Properties; surface property; thickness; Tissue; Titanium; titanium alloy (TiAl6V4); Titanium alloys; X ray photoelectron spectroscopy

ECG noise filtering using wavelets with soft-thresholding methods - Agante Da Silva, P.M.G.; Marques De Sá, J.P. (Computers in CardiologyComput Cardiol, 1999)
In this paper we analyze algorithms for filtering white gaussian noise and 50 Hz power line noise from ECG signals. We used several wavelets to study their effect and efficiency in the filtering process. To deal with these different kinds of noises we used two distinct soft-thresholding techniques: the Donoho's statistical threshold estimator and a method developed by us. This last method exploits one of the wavelet processing main features: time-frequency relation. The de-noising methods led to good filtering results: noise reduction with only minor change of the ECG waveforms as confirmed by the high correlation values between the processed signal and the original one. These good results are due to a wavelet advantage over classical filtering - time-frequency relation - enabling the possibility of filtering noise in the same frequency band of the ECG signal with minimal interference.
Conference code: 56519Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: COCADLanguage of Original Document: EnglishCorrespondence Address: Agante, P.M.; Inst Nacional de Engenharia, Biomedica, Oporto, PortugalReferences: Graps, A., An introduction to wavelets (1995) IEEE Computational Science and Engineering, 2 (2);Donoho, D.L., De-noising by soft-thresholding (1992) Symposium on Wavelet Theory, , Vanderbilt; Daubechies, I., The wavelet transform, time-frequency localization and signal analysis (1990) IEEE Transactions on Information Theory, 36 (5), pp. 961-1005; Chui, C.K., (1992) An Introduction to Wavelets, , Academic Press; Willems, J.L., CSE multilead atlas (1988) Common Standards for Quantitative Electrocardiography (European Concerted Action Project II.2.2), Div. Medical Informatics, , CSE Project Leader, Univ. Hosp. Gasthuisberg, Leuven; Coifman, R., Meyer, Y., Wickerhauser, V., Wavelet Analysis and Signal Processing, , ceres.math.yale.edu, Yale University, available by anonymous ftp at;
Keywords: Algorithms; Electrocardiography; Signal filtering and prediction; Signal interference; Wavelet denoising; White noise

Enhancement of the mechanical properties of a high-density polyethylene - Kalay, G.; Sousa, R.A.; Reis, R.L.; Cunha, A.M.; Bevis, M.J. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 1999)
This paper describes the process optimization in injection molding of high-density polyethylene (HDPE). Both conventional injection molding and shear controlled orientation (SCORIM) were employed in processing. The process optimization was based on design of experiments and complemented with analysis of variance. Mechanical characterization was carried out by tensile testing. Wide-angle X-ray diffraction and differential scanning calorimetry were used for the structural characterization of the moldings. High-density polyethylene exhibits 7.2 GPa Young's modulus and 155 MPa of ultimate tensile strength following the application of SCORIM processing. These results account for a fourfold increase in Young's modulus and a fivefold increase in ultimate tensile strength compared to conventional injection molding. The maintenance of toughness while enhancing stiffness and strength of the SCORIM moldings is attributable to an oriented morphology developed during shear flow, i.e., shish-kebab structure. The frequency of shearing action has the strongest influence on the morphology development. It is also demonstrated that the studied parameters are very much interdependent. It is possible to achieve substantial gains in mechanical properties of HDPE in SCORIM processing without causing a substantial increase in cycle time.
Cited By (since 1996): 48Export Date: 21 November 2012Source: ScopusCODEN: JAPNAdoi: 10.1002/(SICI)1097-4628(19990919)73:12<2473::AID-APP16>3.0.CO;2-OLanguage of Original Document: EnglishCorrespondence Address: Kalay, Gurhan; Brunel Univ, Middlesex, United KingdomReferences: Kalay, G., Allan, P.S., Bevis, M.J., (1997) Kunststoffe, 87, p. 6;Kalay, G., Bevis, M.J., (1997) J Polym Sci Polym Phys, 35, p. 241; Kalay, G., Bevis, M.J., (1997) J Polym Sci Poly Phys, 35, p. 265; Kalay, G., Bevis, M.J., (1997) J Polym Sci Polym Phys, 35, p. 415; Kalay, G., Ogbonna, C.I., Allan, P.S., Bevis, M.J., (1995) Trans IChemE Part A Chem Eng Res Design, 73, p. 798; Keller, A., Kolnaar, H., (1997) Mat Sci Technol, 18, p. 191; Allan, P.S., Bevis, M.J., (1987), British Patent 2170-140-BAllan, P.S., Bevis, M.J., (1990) Composites Manufact, 1, p. 79; Wang, L., Allan, P.S., Bevis, M.J., (1995) Plastics Rubber Composites Process Appl, 23, p. 139; Gil, E.M., Kalay, G., Allan, P.S., Bevis, M.J., (1997) Polymer Process Engineering 97, pp. 40-54. , Coates, P. D., Ed.; The Institute of Materials: London; Ogbonna, C.I., Kalay, G., Allan, P.S., Bevis, M.J., (1995) J Appl Polym Sci, 58, p. 2131; Kubát, J., Månson, J.A., (1983) Polym Eng Sci, 23, p. 86; Kubát, J., Månson, J.A., Rigdahl, M., (1983) Polym Eng Sci, 23, p. 877; Boldizar, A., Kubát, J., Rigdahl, M., (1990) J Appl Polym Sci, 39, p. 63; Guan, Q., Shen, K., Ji, J., Zhu, J., (1995) J Appl Polym Sci, 55, p. 1797; Guan, Q., Shen, K., (1995) Z. Chem J Chinese Univers, 16, p. 1129; Ross, J.P., (1998) Taguchi Techniques for Quality Engineering, , McGraw-Hill: New York; Schmidt, S.R., Launsby, R.G., (1994) Understanding Industrial Designed Experiments, 4th Ed., , Air Academy Press: CO; Montgomery, D.C., (1991) Design and Analysis of Experiments, 3rd Ed., , Wiley: New York
Keywords: differential scanning calorimetry; Elastic moduli; High density polyethylenes; Injection molding; morphology; Optimization; Shear controlled orientation in injection molding; Shear flow; Shish kebab structure; Stiffness; Strength of materials; tensile strength; Tensile testing; Toughness; Wide angle X ray diffraction; X ray diffraction analysis

Flow cytometry analysis of effects of glass on response of osteosarcoma cells to plasma-sprayed hydroxyapatite/CaO-P 2O 5 coatings - Ferraz, M.P.; Knowles, J.C.; Olsen, I.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Multilayered coatings composed of mixtures of hydroxyapatite (HA) and P 2O 5-based bioactive glasses offer potential clinical benefits in orthopedic and dental surgery. In this study double-layer plasma-sprayed coatings were prepared and the biological response evaluated in tissue culture using two human osteosarcoma cell lines, MG63 and HOS TE85 (HOS). The cells were cultured on the materials and the effects on cell growth were determined using a spectrophometric assay of a mitochondrial enzyme that is active in viable cells. While none of the materials influenced the growth of the MG63 cells, the HOS cells appeared to undergo less proliferation on all the HA materials. Flow cytometry analysis was carried out using rabbit antibodies against osteonectin, osteopontin, bone sialoprotein, fibronectin, and collagen type I to measure the effects of the materials on key cellular functions. The results showed that the materials downregulated the expression of these extracellular matrix antigens by MG63 cells whereas they had less effect on the HOS cells compared to the same cells incubated on a plastic surface. Notably, with both cell lines the composite with the higher percentage of glass restored the production of connective tissue proteins to levels that were more similar to those present in the control cells. In this study, double-layer plasma-sprayed coatings were prepared and the biological response evaluated in tissue culture using two human osteosarcoma cell lines, MG63 and HOS TE85 (HOS). The materials downregulated the expression of the extracellular matrix antigens by MG63 cells whereas they had less effect on the HOS cells compared to the same cells incubated on a plastic surface. Notably, with both cell lines the composite with the higher percentage of glass restored the production of connective tissue proteins to levels that were more similar to those present in the control cells.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19991215)47:4<603::AID-JBM18>3.0.CO;2-6PubMed ID: 10497297Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University of London, 256 Gray's Inn Road, London WC1X 8LD, United KingdomChemicals/CAS: Bone Substitutes; Coated Materials, Biocompatible; HydroxyapatitesReferences: Passuti, N., Daculsi, G., Martin, S., Macroporous calcium phosphate ceramics for long bone surgery in human and dogs - Clinical and histological studies (1990) Clinical Implant Materials, pp. 255-258. , Soltesz V, Lee A, editors. Amsterdam: Elsevier Sciesnce Publishers;Legeros, R., Calcium phosphate materials in restorative dentistry. A review (1988) Adv Dent Res, 2, pp. 164-180; Hench, L.L., Bioactive ceramics: From concept to clinic (1992) J Am Ceram Soc, 74, pp. 1487-1510; Conish, H., Aoki, H., Sawai, K., (1981) Science and Medical Applications of Hydroxyapatite, , Tokyo: Takyama Press System Centre Co; Raemdonick, W., Ducheyne, P., Meester, P., Calcium phosphate ceramics (1984) Metal and Ceramic Materials, pp. 143-166. , Ducheyne P, Hastings GW, editors. Boca Raton, FL: CRC Press; Rey, C., Freche, M., Heughebaert, M., Vignoles, M., Apatite chemistry in biomaterial preparation, shaping and biological behaviour (1991) 4th Symposium on Ceramics in Medicine - Bioceramics, 4, pp. 57-64. , Bonfield W, Hastings GW, Tanner KE, editors. London: Butterworth-Heinemann; Nagase, M., Abe, Y., Udagwa, E., Toxicity of silica-containing calcium phosphate glasses demonstrated in mice (1992) Biomaterials, 13, pp. 172-175; Burnie, J., Gilchrist, T., Controlled released glass - A new biomaterial (1983) Ceramics in Surgery, pp. 169-176. , Vicenzini P, editor. Amsterdam: Elsevier Science Publishers; Jha, L.J., Santos, J.D., Knowles, J.C., Characterization of apatite layer formation on P 2O 5-CaO, P 2O 5-CaO-Na 2O, P 2O 5-CaO-Na 2O-Al 2O 3 glass hydroxyapatite composites (1996) J Biomed Mater Res, 31, pp. 481-486; Rawlings, R.D., Rogers, P.S., Stokes, P.M., Glass-ceramics containing apatite (1987) High Tech Ceramics, pp. 73-82. , Vicenzini P, editor. Amsterdam: Elsevier Science Publishers; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Santos, J.D., Lakhan, J.J., Monteiro, F.J., Surface modifications of glass-reinforced hydroxyapatite composites (1995) Biomaterials, 16, pp. 521-526; Ferraz, M.P., Monteiro, F.J., Santos, J.D., In vitro bioactivity and osteocompatibility evaluation of plasma sprayed hydroxyapatite/glass composite coatings onto Ti-6AL-4V substrates (1997) 9th International Conference on Biomedical Engineering, pp. 557-559. , Goh JCH, editor. Singapore: BAC Printers; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Plasma-sprayed coatings of tetracalcium phosphate, hydroxylapatite, and α-TCP on titanium alloy: An interface study (1991) J Biomed Mater Res, 25, pp. 53-65; Jansen, J.A., Van Der Waerden, J.P., Wolke, J.G., Histologic investigation of the biologic behavior of different hydroxyapatite plasma-sprayed coatings in rabbits (1993) J Biomed Mater Res, 14, pp. 603-610; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the bone-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., Comparative biological properties of HA plasma-sprayed coatings having different crystallinities (1994) J Mater Sci Mater Med, 5, pp. 11-17; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., Cytotoxicity investigations of plasma-sprayed calcium-phosphate coatings (1994) J Mater Sci Mater Med, 5, pp. 371-375; Courteney-Harris, R.G., Kayser, M.V., Downes, S., Comparison of the early production of extracellular matrix on dense hydroxyapatite and hydroxyapatite-coated titanium in cell and organ culture (1995) Biomaterials, 16, pp. 489-495; Labat, B., Chanson, A., Frey, J., Effects of γ-alumina and hydroxyapatite coatings on the growth and metabolism of human osteoblasts (1995) J Biomed Mater Res, 29, pp. 1397-1401; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., Adult human bone cells derived from jaw bones cultured on plasma-sprayed or polished surfaces to titanium or hydroxyapatite discs (1996) J Mater Sci Mater Med, 7, pp. 21-28; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Biomater, 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci Mater Med, 7, pp. 637-643; Macey, M.G., (1994) Flow Cytometry - Clinical Applications, , Oxford, UK: Blackwell Scientific Publications; Shapiro, H.M., (1995) Practical Flow Cytometry, , New York: Wiley-Liss; Melamed, M.R., Lindmo, T., Mendelsohn, M.L., (1990) Flow Cytometry and Sorting, , New York: Wiley-Liss; Muirhead, K.A., Horan, P.K., Applications of flow cytometry to tissue culture systems (1983) Adv Cell Culture, 3, pp. 57-91; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Pande, G., Kumar, N.A., Manogaran, P.S., Flow cytometric study of changes in intracellular free calcium during the cell cycle (1996) Cytometry, 24, pp. 55-63; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphyromonas gingivalis by a lps specific monoclonal antibody (1994) J Periodontol, 65, pp. 309-315; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J Dent Res, 77, pp. 555-564; Abraham, D., Lupoli, S., McWhirter, A., Plater-Zyberk, C., Piela, T.H., Korn, J., Olsen, I., Black, C., Expression and function of surface antigens on scleroderma fibroblasts (1991) Arthritis Rheum, 34, pp. 1164-1172; Beauchamp, J.R., Abraham, D.J., Bou-Gharios, G., Partridge, T.A., Olsen, I., Expression and function of adhesion molecules during differentiation of human skeletal muscle in culture (1992) Am J Pathol, 140, pp. 387-401; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin Chim Acta, 231, pp. 69-78; Lopes, M.A., Knowles, J.C., Hing, K.A., Santos, J.D., Monteiro, F.J., Olsen, I., Biological evaluation of glass reinforced hydroxyapatite by flow cytometry (1997) 10th Symposium on Ceramics in Medicine-bioceramics, 10, pp. 575-578. , Sedel L, Rey C, editors. Cambridge, UK: University Press; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Sandy, J., Davies, M., Prime, S., Farndale, R., Signal pathways that transduce growth factor-stimulated mitogenesis in bone cells (1998) Bone, 23, pp. 17-26
Keywords: Animals; Antibodies; antigen expression; article; Bioassay; Biomaterials; Bone cells; Bone sialoprotein; Bone Substitutes; calcium phosphate; cancer cell culture; Cell Division; cell function; cell granule; cell growth; cell proliferation; Cell size; Cells; Coated Materials, Biocompatible; Collagen; collagen type 1; connective tissue; controlled study; dentistry; enzyme activity; Enzymes; Fibronectin; flow cytometry; Flow cytometry analysis; glass; Growth kinetics; human; human cell; Humans; hydroxyapatite; Hydroxyapatite-glass; Hydroxyapatites; Incubation; Mitochondrial enzyme; orthopedics; Osteoblasts; osteonectin; Osteopontin; Osteosarcoma; osteosarcoma cell; Osteosarcoma cells; Phosphates; Proliferation; Proteins; Rabbits; sialoprotein; Spectrophometric assay; Tissue culture; Tumor Cells, Cultured

Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics - Lopes, M.A.; Monteiro, F.J.; Santos, J.D. (BiomaterialsBiomaterials, 1999)
Fracture toughness and hardness properties of CaO-P 2O 5 glass-reinforced hydroxyapatite composites have been assessed using indentation techniques and results calculated according to Laugier and Evans' equations. Both properties showed to be dependent upon several microstructural characteristics, namely residual porosity and the percentage of secondary β and α tricalcium phosphate phases in the structure of the composites. Composites presented a Palmqvist-type indentation crack system, which is the specific crack system addressed by Laugier's approach. Fracture toughness determinations according to Evan's equation, which is a universal one and adapted to both median and Palmqvist crack systems, did not correlate well with Laugier determinations. Copyright (C) 1999 Elsevier Science Ltd. Fracture toughness and hardness properties of CaO-P 2O 5 glass-reinforced hydroxyapatite composites have been assessed using indentation techniques and results calculated according to Laugier and Evans' equations. Both properties showed to be dependent upon several microstructural characteristics, namely residual porosity and the percentage of secondary β and α tricalcium phosphate phases in the structure of the composites. Composites presented a Palmqvist-type indentation crack system, which is the specific crack system addressed by Laugier's approach. Fracture toughness determinations according to Evan's equation, which is a universal one and adapted to both median and Palmqvist crack systems, did not correlate well with Laugier determinations.
Cited By (since 1996): 65Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00112-XPubMed ID: 10535820Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratorio de Biomateriais, Instituto de Engenharia Biomedica, INEB, Rua do Campo Alegre 823, 4150 Porto, PortugalChemicals/CAS: alpha-tricalcium phosphate; Biocompatible Materials; calcium phosphate, 10103-46-5; Calcium Phosphates; Composite Resins; dicalcium phosphate anhydrous, 7757-93-9; Durapatite, 1306-06-5; monocalcium phosphate; tetracalcium phosphateReferences: Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812;Martin, R.I., Brown, P.W., Mechanical properties of hydroxyapatite formed at physiological temperature (1995) J Mater Sci Mater Med, 6, pp. 138-143; Aoki, H., (1994) Medical Applications of Hydroxyapatite, pp. 90-173. , Tokyo, Missouri, USA: Ishiyaku EuroAmerica Inc; Yamamuro, T., Hench, L., Wilson, J., Calcium phosphate and hydroxyapatite ceramics (1990) In: Handbook of Bioactive Ceramics, 2, pp. 273-335. , editors. Florida: CRC Press Inc; Cao, W., Hench, L.L., Bioactive materials (1996) Ceramics Int, 22, pp. 493-507; Davidge, R.W., (1979) Mechanical Behaviour of Ceramics, , Cambridge: Cambridge University Press; Orange, G., Liang, K.M., Crack resistance and fracture toughness of alumina and zirconia ceramics: comparisons of notched-beam and indent techniques (1988) Science of Ceramics, 14, pp. 709-714. , Amsterdam: Elsevier; Niihara, K., Morena, R., Hasselman, D.P.H., Evaluation of K IC of brittle solids by the indentation method with low crack-to-indent ratios (1982) J Mater Sci Lett, 1, pp. 13-16; Evans, G., Fracture toughness: The role of indentation techniques (1979) Fracture Mechanics Applied to Brittle Materials ASTM STP 678, pp. 112-135. , S.W. Freiman. Blasksbaurg: American Society for Testing and Materials; Anstis, G.R., Chantikul, P., Lawn, B.R., Marshall, D.B., A critical evaluation of indentation techniques for measuring fracture toughness: I. Direct crack measurements (1981) J Am Ceram Soc, 64 (9), pp. 533-538; Chantikul, P., Anstis, G.R., Lawn, B.R., Marshall, D.B., A critical evaluation of indentation techniques for measuring fracture toughness: II. Strength method (1981) J Am Ceram Soc, 64 (9), pp. 539-543; Evans, G., Charles, E.A., Fracture toughness determinations by indentation (1976) J Am Ceram Soc, 59 (78), pp. 371-372; Marion, R.H., Use of indentation fracture to determine fracture toughness (1979) Fracture Mechanics Applied to Brittle Materials, ASTM STP 678, pp. 103-111. , S.W. Freiman. Blasksbaurg: American Society for Testing and Materials; Knowles, J.C., Talal, S., Santos, J.D., Sintering effects in a glass reinforced hydroxyapatite (1996) Biomaterials, 17, pp. 1437-1442; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength (1999) J Appl Biomater, , in press; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 4, pp. 649-656; Santos, D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15 (1), pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Laugier, M.T., New formula for indentation toughness in ceramics (1987) J Mater Sci Lett, 6, pp. 355-356; Ampiro, R., (1958) Acta Anat, 3, p. 161; De With, G., Van Dijk, H.J.A., Hattu, N., Prijs, K., Preparation, microstructure and mechanical properties of dense polycrystalline hydroxyapatite (1981) J Mater Sci, 16, pp. 1592-1598; German, R.M., (1985) Liquid Phase Sintering, , Oxford: Plenum Press; Rice, R.W., Microstructure dependence of mechanical behaviour (1977) Treatise on Materials Science and Technology, 11. , MacCrone R.K. New York: Academic Press; Rice, R.W., Grain size and porosity dependence of ceramic fracture energy and toughness at 22°C (1996) J Mater Sci, 31, pp. 1969-1983; Lankford, J., Indentation microfracture in the Palmqvist crack regime: Implications for fracture toughness evaluation by the indentation method (1982) J Mater Sci Lett, 1, pp. 493-495; Li, Z., Ghosh, A.A., Kobayashi, A.S., Bradt, R.C., Indentation fracture toughness of sintered silicon carbide in the Palmqvist crack regime (1989) J Am Ceram Soc, 72 (6), pp. 904-911; Lawn, R., Marshall, D.B., Hardness, toughness and brittleness: An indentation analysis (1980) J Am Ceram Soc, 62 (78), pp. 347-350; Niihara, K., A fracture mechanics analysis of indentation-induced Palmqvist crack in ceramics (1983) J Mater Sci Lett, 2, pp. 221-223; Plannel, J.A., Vallet-Regi, M., Fernandez, E., Driessens, F.C.M., Fracture toughness evaluation of sintered hydroxyapatite (1994) Bioceramics 7, Proceedings of the Seventh International Symposium on Ceramics in Medicine, pp. 18-22. , In: Andersson OH, Yli-Urpo A, editors; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Science. Tokyo: Takayama Press System Center Co. Inc; Hauber, R.A., Anderson, R.M., Engineering properties of glass-matrix composites In: Ceramics and Glasses, Engineered Materials Handbook, pp. 858-869. , USA: ASM Publication; Barsoum, M., Mechanical properties: Fast fracture (1997) Fundamentals of Ceramics. Series in Materials Science and Engineering, pp. 391-439. , New York: McGraw-Hill; Slosarczyk, A., Bia Oskorski, J., Hardness and fracture toughness of dense calcium-phosphate based materials (1998) J Mater Sci Mater Med, 9, pp. 103-108
Keywords: article; Biocompatible Materials; Biomaterials; calcium phosphate; Calcium phosphates; ceramics; Composite materials; Composite Resins; Cracks; Durapatite; Evan's equation; Fracture toughness; glass; hardness; hydroxyapatite; Hydroxyapatite-glass composites; Indentation techniques; Kinetics; Laugier equations; material state; mechanical stress; Microscopy, Electron, Scanning; Microstructure; Palmqvist crack systems; Phosphate minerals; porosity; priority journal; Stress, Mechanical; tensile strength; Tricalcium phosphate

Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength - Lopes, M.A.; Monteiro, F.J.; Santos, J.D. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
CaO-P 2O 5 glasses with additions of MgO and CaF 2 were used as a sintering aid of hydroxyapatite, and glass-reinforced hydroxyapatite composites obtained. Glasses promoted significant changes in the microstructure of the composites, namely with the formation of tricalcium phosphate secondary phases, β and α-TCP. Quantitative phase analysis was performed by the Rietveld method using General Structure Analysis Software. Grain size measurements were carried out on SEM photomicrographs, using a planimetric procedure according to ASTM E 112-88. Flexural bending strength was determined from concentric ring-on-ring testing. Flexural bending strength (FBS) of glass-reinforced hydroxyapatite composites was found to be about twice or three times higher than that of unreinforced hydroxyapatite and tended to depend more on porosity and β and α-TCP secondary phases, rather than on grain size. Traces of α-tricalcium phosphate significantly enhanced the strength of the composites. Using the rule of mixtures to estimate the zero porosity bending strength, the Duckworth-Knudsen model applied to the composites gave a porosity correction factor, b, with a value of 4.02. Weibull statistics were also used to analyze biaxial strength data and the level of reinforcement obtained by comparing failure probability for the composites and for the unreinforced hydroxyapatite. Lower activation energies for grain growth were observed for the composites compared to unreinforced hydroxyapatite, which should be attributed to the presence of a liquid glassy phase that promotes atomic diffusion during the sintering process. CaO-P 2O 5 glasses with additions of MgO and CaF 2 were used as a sintering aid of hydroxyapatite, and glass-reinforced hydroxyapatite composites obtained. Glasses promoted significant changes in the microstructure of the composites, namely with the formation of tricalcium phosphate secondary phases, β and α-TCP. Quantitative phase analysis was performed by the Rietveld method using General Structure Analysis Software. Grain size measurements were carried out on SEM photomicrographs, using a planimetric procedure according to ASTM E 112-88. Flexural bending strength was determined from concentric ring-on-ring testing. Flexural bending strength (FBS) of glass-reinforced hydroxyapatite composites was found to be about twice or three times higher than that of unreinforced hydroxyapatite and tended to depend more on porosity and β and α-TCP secondary phases, rather than on grain size. Traces of α-tricalcium phosphate significantly enhanced the strength of the composites. Using the rule of mixtures to estimate the zero porosity bending strength, the Duckworth-Knudsen model applied to the composites gave a porosity correction factor, b, with a value of 4.02. Weibull statistics were also used to analyze biaxial strength data and the level of reinforcement obtained by comparing failure probability for the composites and for the unreinforced hydroxyapatite. Lower activation energies for grain growth were observed for the composites compared to unreinforced hydroxyapatite, which should be attributed to the presence of a liquid glassy phase that promotes atomic diffusion during the sintering process.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(1999)48:5<734::AID-JBM20>3.0.CO;2-2PubMed ID: 10490690Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-Instituto Engenharia Biomedica, Laboratorio de Biomateriais, Rua do Campo Alegre, 823, 4150 Porto, PortugalChemicals/CAS: alpha-tricalcium phosphate; Biocompatible Materials; calcium phosphate, 10103-46-5; Calcium Phosphates; dicalcium phosphate anhydrous, 7757-93-9; Hydroxyapatites; monocalcium phosphate; tetracalcium phosphateReferences: Yamamuro, Y., Hench, L.L., Wilson, J., (1990) CRC Handbook of Bioactive Ceramics, , Boca Raton, FL: CRC;Rice, R.W., Microstructure dependence of mechanical behaviour (1977) Treatise on Materials Science and Technology, 11. , MacCrone RK, editor. New York: Academic; Rice, R.W., Grain size and porosity dependence of ceramic fracture energy and toughness at 22°C (1996) J Mat Sci, 31, pp. 1969-1983; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Wayne, S.F., Buljan, S.T., Microstructure and wear resistance of silicon nitride composites (1994) Friction and Wear of Ceramics, p. 261. , Jahanmir S, editor. New York: Marcel Dekker; Kaysser, W.A., Sprissler, M., Handwerker, C.A., Blendell, J.E., Effect of liquid phase on the morphology of grain growth of alumina (1987) J Am Ceram Soc, 70, pp. 339-343; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Soltesz, U., Ritcher, H., Kienzler, R., The concentric-ring test and its applications for determining the surface strength of ceramics (1987) High Tech Ceram, pp. 149-159. , Amsterdam: Elsevier; Murtage, B., (1981) Advance Linear Programming, , New York: McGraw-Hill; Cha'tal, V., (1990) Linear Programming, , New York: Freeman; Davidge, R.W., (1986) Mechanical Behaviour of Ceramics, , Cambridge: Cambridge Univ Press; German, R.M., (1985) Liquid Phase Sintering, , New York: Plenum; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812; Fanovich, M.A., Lopes, J.M.P., Influence of temperature and additives on the microstructure and sintering behaviour of hydroxyapatites with different Ca/P ratios (1998) J Mat Sci Mat Med, 9, pp. 53-60; Jarcho, M., Bolen, C.H., Bobik, J., Kay, J.F., Doremus, R.H., Hydroxyapatite synthesis and characterisation in dense polycrystalline form (1976) J Mat Sci, 11, pp. 2027-2035; Van Landuyt, P., Li, F., Keustermans, J.P., Streydio, J.M., Delnnay, F., Munting, E., The influence of high sintering temperatures on the mechanical properties of hydroxyapatite (1995) J Mat Sci Mat Med, 6, pp. 8-13; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Layer; Chawla, K.K., (1993) Ceramic Matrix Composites, , London, UK: Chapman Hall; Barsoum, M., Fundamentals of Ceramics, , New York: McGraw-Hill; 1997
Keywords: article; atom; Bending (deformation); Biocompatibility; Biocompatible Materials; Biomaterials; calcium fluoride; calcium phosphate; Calcium phosphates; Composite materials; Densification; Dental application; dentistry; Duckworth-Knudsen model; glass; Glass reinforced hydroxyapatite; Humans; hydroxyapatite; Hydroxyapatite-glass composites; Hydroxyapatites; Implants (surgical); Magnesium Oxide; mathematical analysis; Mechanical strength; Mechanics; Medical applications; Microstructure; orthopedics; Phase composition; physical chemistry; porosity; Scanning electron microscopy; Strength of materials; tensile strength; Tissue; Tricalcium phosphate

Histological effects of iron accumulation on mice liver and spleen after administration of a metallic solution - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (BiomaterialsBiomaterials, 1999)
Special attention has been focused on the toxicity of some metallic species released from implanted materials, which accumulate in vital organs over long periods of time. A set of experiments with mice was designed to investigate the individual effects caused by iron in the liver and spleen. Histological features of these organs were evaluated and slight morphological changes were observed during the treatment time suggesting a negative correlation with the duration of the iron treatment. In addition, to associate the histological changes in the organs with iron accumulation an electrochemical method, adsorptive stripping voltammetry, was chosen to quantify the iron levels in these mentioned organs. The accuracy of the proposed method was checked by atomic absorption spectrometry. Both organs showed elevated concentrations of iron, nearly twofold, 7 days after iron administration compared to control organs.Special attention has been focused on the toxicity of some metallic species released from implanted materials, which accumulate in vital organs over long periods of time. A set of experiments with mice was designed to investigate the individual effects caused by iron in the liver and spleen. Histological features of these organs were evaluated and slight morphological changes were observed during the treatment time suggesting a negative correlation with the duration of the iron treatment. In addition, to associate the histological changes in the organs with iron accumulation an electrochemical method, adsorptive stripping voltammetry, was chosen to quantify the iron levels in these mentioned organs. The accuracy of the proposed method was checked by atomic absorption spectrometry. Both organs showed elevated concentrations of iron, nearly twofold, 7 days after iron administration compared to control organs.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(99)00124-6PubMed ID: 10555088Language of Original Document: EnglishCorrespondence Address: Pereira, M.C.; Departamento de Engenharia Quimica, Faculdade de Engenharia, Universidade do Porto, Rua dos Bragas, 4050-123 Porto, Portugal; email: mcsp@fe.up.ptChemicals/CAS: Iron, 7439-89-6; SolutionsReferences: Rheinold, J.B., Trace elements - A selective survey (1975) Clin Chem, 21, p. 476;Crichton, R.R., Ward, R.J., Structure and molecular biology of iron binding-proteins and the regulation of free iron pools (1992) Iron and Human Diseases, pp. 23-75. , R.B. Lauffer. Boca Raton: CRC Press Inc; Lynch, S.R., Lipschitz, D.A., Bothwell, T.H., Charlton, R.W., Iron and the reticulo-endothelial system (1974) Iron in Biochemistry and Medicine, p. 563. , A. Jacobs, & M. Worwood. London: Academic Press; Black, J., Mineral metabolism (1981) Biological Performance of Materials: Fundamentals of Biocompatibility. Biomedical Engineering and Instrumentation, 8, pp. 158-168. , R. Plonsey, Katz J.L. New York: Marcel Dekker; Sutow, E.J., Pollack, S.R., The biocompatibility of certain stainless steels (1981) Biocompatibility of Clinical Implant Materials, pp. 77-98. , D.F. Williams. Boca Raton, FL: CRC Press; Winter, G.D., Tissue reactions to metallic wear and corrosion products in human patients (1974) J Biomed Mater Res Symp, 5, pp. 11-26; Winter, G.D., Wear and corrosion products in tissues and the reactions they provoke (1976) Biocompatibility of Implant Materials, pp. 28-54. , In: Williams, DF, editor London; Ferguson A.B., Jr., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J Bone Jt Surg a, 42, pp. 77-90; Pohler, O.E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, pp. 196-197. , In: Rubin LR, editor London: The C.V. Mosby Company; Lux, F., Zeisler, R., Investigations of the corrosive deposition of components of metal implants and the behaviour of biological trace elements in metallosis tissue by means of instrumental multi-element activation analysis (1974) J Radioanal Chem, 19, pp. 289-297; Traisnel, M., Le Maguer, D., Hildebrand, H.F., Iost, A., Corrosion of surgical implants (1990) Clin Mater, 5, pp. 309-318; Gosztonyi, E., (1983) Iron Metabolism, p. 339. , New York: Plenum Press; Weinberg, E.D., Cellular acquisition of iron and the iron-withholding defense against microbial and neoplastic invasion (1992) Iron and Human Diseases, pp. 179-207. , R.B. Lauffer. Boca Raton, FL: CRC Press Inc; Pereira, M.L., Pereira, M.C., Sousa, J.P., Evaluation of nickel effects on mouse liver: Tissue response and metal ion accumulation (1995) Biomed Lett, 52, pp. 235-244; Pereira, M.C., Pereira, M.L., Sousa, J.P., Evaluation of nickel toxicity on liver, spleen and kidney of mice after administration of high-dose metal ion (1998) J Biomed Mater Res, 40, pp. 40-47; Pereira, M.C., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using microelectrodes (1997) Electroanalysis, 9, pp. 150-154; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping measurements of iron accumulation in mice kidney using microelectrodes and histological features (1998) J Trace Elements Med Biol, 12, pp. 50-55; Van Den Berg, C.M.G., Huang, Z.Q., Determination of iron in seawater using cathodic stripping voltammetry proceeded by adsorptive collection with the hanging mercury drop electrode (1984) J Electroanal Chem, 177, pp. 269-280; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 223-247. , A.C. Fraker, & C.D. Griffin. Philadelphia: American Society for Testing and Materials; Barbosa, M.A., (1991) Biomaterials Degradation, p. 227. , Barbosa M.A. The Netherlands: Elsevier Science Publisher; Steinemann, S.G., Corrosion of surgical implants in vivo and in vitro tests (1980) Evaluation of Biomaterials, pp. 1-34. , In: Winter GD et al., editors UK: John Wiley & Sons Inc; Smith, G.K., Systemic aspects of metallic implant degradation (1983) Biomaterials in Reconstructive Surgery, pp. 229-242. , In: Rubin LR, London: The C.V. Mosby Company; Britton, S.R., Ramm, G.A., Olynyk, J., Singh, R., O'Neill, R., Bacon, B.R., Pathophysiology of iron toxicity (1994) Progress in Iron Research, pp. 239-253. , C. et al. Hershko. New York: Plenum Press
Keywords: Absorption spectroscopy; accuracy; Adsorption; Adsorptive stripping voltametry; Adsorptive stripping voltammetry; animal experiment; animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Atomic spectroscopy; bioaccumulation; biomaterial; controlled study; Corrosion; electrochemistry; histology; histopathology; Implants (surgical); Injections, Subcutaneous; Iron; iron metabolism; Kinetics; Liver; liver toxicity; male; metal implantation; Mice; morphology; mouse; nonhuman; Organ Size; potentiometry; priority journal; quantitative assay; Solutions; Spleen; Stainless steel; tissue distribution; toxicity

Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites - Lopes, M.A.; Monteiro, F.J.; Santos, J.D.; Serro, A.P.; Saramago, B. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
Wettability and zeta potential studies were performed to characterize the hydrophobicity, surface tension, and surface charge of P 2O 5-glass- reinforced hydroxyapatite composites. Quantitative phase analysis was performed by the Rietveld method using GSAS software applied to X-ray diffractograms. Surface charge was assessed by zeta potential measurements. Protein adsorption studies were performed using vitronectin. Contact angles and surface tensions variation with time were determined by the sessile and pendent drop techniques, respectively, using ADSA-P software. The highest (- 18.1 mV) and lowest (-28.7 mV) values of zeta potential were found for hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP), respectively, with composite materials presenting values in between. All studied bioceramic materials showed similar solid surface tension. For HA and β-TCP, solid surface tensions of 46.7 and 45.3 mJ/m 2, respectively, were obtained, while composites presented intermediate surface tension values. The dispersive component of surface tension was the predominant one for all materials studied. Adhesion work values between the vitronectin solution and HA and β- TCP were found to be 79.8 and 88.0 mJ/m 2, respectively, while the 4.0 wt % glass composites showed slightly lower values than the 2.5 wt % ones. The presence of β-TCP influenced surface charge, hydrophobicity, and protein adsorption of the glass-reinforced HA composites, and therefore indirectly affected cell-biomaterial interactions. The hydrophobicity, surface tension, and surface charge of P 2O 5-glass-reinforced hydroxyapatite (HA) composites were characterized through wettability and zeta potential studies. The highest and lowest values of zeta potential were found for HA and β-TCP. All studied bioceramic materials showed similar solid surface tension. The presence of β-TCP indirectly affected cell-biomaterial interactions.
Cited By (since 1996): 46Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19990615)45:4<370::AID-JBM12>3.0.CO;2-0PubMed ID: 10321710Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB, University of Porto, Rua do Campo Alegre, 823, 4150 Porto, PortugalChemicals/CAS: Biocompatible Materials; Calcium Phosphates; Hydroxyapatites; Proteins; VitronectinReferences: Yamamuro, Y., Hench, L.L., Wilson, J., (1990) CRC Handbook of Bioactive Ceramics, , Boca Raton, FL: CRC Press;Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterization of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Aoki, H., Medical applications of hydroxyapatite (1991) Science and Medical Applications of Hydroxyapatite, pp. 1-214. , Aoki H, Sawai K, editors. Tokyo: Takyama Press System Center; Akao, M., Aoki, H., Kato, K., Mechanical properties of sintered hydroxyapatite for prosthetic applications (1981) J Mater Sci, 16, pp. 809-812; Davies, J.E., The importance and measurement of surface charge species in cell behaviour at the biomaterial interface (1988) Surface Characterization of Biomaterials, pp. 219-234. , Ratner BD. New York: Elsevier; Ratner, B.D., Biomaterial surfaces (1987) J Biomed Mater Res Appl Biomat, 21, pp. 59-90; Manson, S.R., Harker, L.A., Ratner, B.D., Hoffman, A.S., Evaluation of artificial surfaces with a non human primate model of arterial thrombosis (1980) J Lab Clin Med, 95, pp. 289-304; Grinnell, F., Milamand, M., Srere, P.A., Studies on cell adhesion (1972) Arch biochem biophys, 153, pp. 193-198; Chang, S.K., Hum, O.S., Moscarello, Ma., Neumann, A.W., Zing, W., Leutheusser, M.J., Ruegsegger, B., Platelet adhesion to solid surfaces: The effect of plasma proteins and substrate wettability (1997) Med Progr Technol, 5, pp. 57-66; Agathopoulos, S., Nikolopoulos, P., Determination of the energy of the interactions oxides and biological liquids (1995) Fourth Euro Ceramics, 8, pp. 319-324. , Ravaglioli A, editor; Lapin, M., Warocquier-Clérout, R., Legris, C., Degrange, M., Luizard, M.F.S., Correlation between roughness and wettability, cell adhesion and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Williams, D.F., Bagnall, R.D., Adsorption of proteins on polymers and its role in the response of soft tissue (1998) Fundamental Aspects of Biocompatibility, 2, pp. 113-127. , Williams DF, editor. Boca Raton, FL: CRC Press; Dimitrov, S., Krachevsky, P.A., Nikolov, A.D., Noshi, H., Matsumoto, M., Contact angle measurements with sessile drops and bubbles (1991) J Colloid Interface Sci, 145, pp. 279-282; Adamson, W., (1990) Physical chemistry of surfaces. 5th edition, pp. 4-52. , New York: Wiley; Young, T., (1835) Miscellaneous Works, 1, p. 418. , Peacock G, editor London: Murray; Young, T., (1805) Philos Trans R Soc Lond, 95, p. 65; Correia, N.T., Ramos, J.M., Saramago, B., Calado, J., Estimation of the surface tension of a solid: Application to a liquid crystalline (1997) J Colloid Interface Sci, 189, pp. 361-369; Owens, D.K., Wendt, R.D., Estimation of the surface free energy of polymers (1969) J Appl Polym Sci, 13, p. 1741; Schrader, M.E., Young dupré revisited (1995) Langmuir, 11, p. 3585; Kowalchuk, R.M., Pollack, S.R., Ducheyne, P., King, L.A., Particle microelectrophoresis of calcium-deficient hydroxyapatite: Solution composition and kinetics effects (1993) J Biomed Mater Res, 27, pp. 783-790; Ducheyne, P., Kim, C.S., Pollack, S.R., The effect of phase differences on the time dependent variation of the zeta potential of hydroxyapatite (1992) J Biomed Mater Res, 26, pp. 147-168; Suzuki, T., Nishizawa, K., Yokogawa, Y., Kameyama, T., Time-dependent variation of the surface structure of bioceramics in tissue culture medium and the effect on adhesiveness of cells (1996) J Ferment Bioeng, 81, pp. 226-232; Susuki, T., Yamamoto, T., Yoriyama, M., Kameyama, T., Surface instability of calcium phosphates ceramics in tissue culture medium and the effect on adhesion and growth of anchorage-dependent animal cells (1997) J Biomed Mater Res, 34, pp. 507-517; Hay, H., (1991) Cell Biology of Extracellular Matrix. 2nd Edition, pp. 127-129. , New York: Plenum Press; Seiffert, D., Detection of vitronectin in mineralized bone matrix (1986) J Histochem Cytochem, 44, pp. 275-280; Rodan, G.A., Introduction to bone biology (1992) Bone, 12, p. 53; Young, M.E., Kerr, J.M., Ibaraki, K., Heegaard, A.M., Gehron, R.P., Structure, expression and regulation of the major matrix proteins of bone (1992) Clin Orthop Rel Res, 281, p. 275; Formigli, L., Zecchi, S., Benvenuti, S., Brandi, M.L., Cell to cell interaction on bone tissue (1992) Ann NY Acad Sci, 673, p. 120; Underwound, P.A., Bennett, F.A., A comparison of the biological activities of the cell-adhesive proteins vitronectin and fibronectin (1989) J Cell Sci, 93, pp. 641-649; Hayman, E.G., Pierschbacher, M.D., Suzuki, S., Ruoslahti, E., Vitronectin: A major cell attachment-promoting protein in foetal bovine serum (1985) Exp Cell Res, 160, pp. 245-250; Lopes, Ma., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Lopes, Ma., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Cheng, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation of axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Colloids Surf, 43, pp. 151-167; Cheng, P., Neumann, A.W., Computational evaluation of axisymmetric drop shape analysis-profile (ADSA-P) (1992) Colloids Surf, 62, pp. 297-306; Saramago, B., Teixeira, M.J., Rosa, M.E., Bordadao, J.C., Influence of the wetting properties of polymeric adhesives on the mechanical behaviour of cork agglomerates (1996) A Adhes Sci Technol, 10, pp. 1111-1127; Voigt, A., Thiel, O., Williams, D., Policova, Z., Zingg, W., Neumann, A.W., Asymmetric drop shape analysis (ADSA) applied to protein solution (1991) Colloid Surf, 58, p. 315; Williams, R.L., Hunt, J.A., Tengvall, P., Fibroblast adhesion onto methyl-silica gradients with and without preadsorbed proteins (1995) J Biomed Mater Res, 29, pp. 1545-1555; Hench, L.L., Ethridge, E.C., (1982) Biomaterials: An Interfacial Approach, , New York: Academic Press; Horbert, T.A., Brash, J.L., Proteins at interfaces. II. Fundamentals and applications (1994) ACS Symposium, 602, pp. 1-23. , Chapter 1, Chapter 7; Vogler, E.A., Interfacial chemistry in biomaterials science (1993) Wettability, 49, pp. 183-250. , Berg JC, editor New York: Marcel Dekker; Chapter 4
Keywords: Adhesion; Adsorption; Algorithms; article; Biocompatible Materials; biomaterial; Biomaterials; Bone; Calcium Compounds; calcium phosphate; Calcium phosphates; Cells; Chemical analysis; Chemistry, Physical; Composite materials; Contact angle; glass; Glass reinforced hydroxyapatite composites; hydrophobicity; hydroxyapatite; Hydroxyapatite-glass composites; Hydroxyapatites; implant; Implants (surgical); Interfacial energy; Phosphorus Compounds; Protein adsorption; Proteins; Surface charge; Surface Properties; surface property; Surface tension; Tricalcium phosphate; Vitronectin; wettability; X-Ray Diffraction; Zeta potential

In vitro growth and differentiation of osteoblast-like human bone marrow cells on glass reinforced hydroxyapatite plasma-sprayed coatings - Ferraz, M.P.; Fernandes, M.H.; Cabral, A.T.; Santos, J.D.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1999)
Human osteoblastic bone marrow cells were cultured far periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorus in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples showed cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow eel Is was closer to that observed in control cultures.Human osteoblastic bone marrow cells were cultured for periods of up to 28 days in control conditions and on the surface of a glass reinforced hydroxyapatite composite (HA/G1) and commercial hydroxyapatite (HA) plasma-sprayed coatings, in the 'as-received' condition and after immersion treatment in culture medium for 21 days. Cultures were characterized for total protein content and alkaline phosphatase activity. Scanning electron microscope analyses were performed on control cultures, seeded materials and materials incubated in the absence of cells. Culture media were analyzed for total and ionized calcium and phosphorus concentrations throughout the incubation period. Immersion of HA/G1 and HA coatings in culture medium resulted in significant alterations to the levels of calcium and phosphorous in the medium, leading to surface modifications. However, seeded material samples showed significant differences in the pattern of variation of the levels of these species. Cell proliferation was observed in the 'as-received' HA/G1 composite, but cell mediated formation of mineral deposits was not proved. In contrast, 'as-received' HA hardly supported cell growth. Previously immersed material samples cell proliferation and evidence of biological formation of mineral deposits. However, the HA/G1 composite presented better surface characteristics for cell growth as the behavior of bone marrow cells was closer to that observed in control cultures.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008924516146Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Institute of Biomedical Engineering, Faculties of Dental Medicine, Universidade do Porto, 4200 Porto, PortugalChemicals/CAS: alkaline phosphatase, 9001-78-9; calcium ion, 14127-61-8; hydroxyapatite, 1306-06-5, 51198-94-8; phosphorus, 7723-14-0; protein, 67254-75-5References: Passuti, N., Daculsi, G., Martin, S., (1990) Clinical Implant Materials, p. 255. , edited by V. Soltesz and A. Lee (Elsevier, Amsterdam);Legeros, R., (1988) Adv. Dental Res., 2, p. 164; Hench, L.L., (1992) J. Amer. Ceram. Soc., 74, p. 1487; Kokubo, T., (1993) Bone-Bonding Biomaterals, p. 31. , edited by P. Ducheyne, T. Kokubo and C. A. Blitterswijk (Reed Health-Care Comunications, Leiden, The Netherlands); Daculsi, G., Legeros, R.Z., Henghebaert, M., Barbieux, I., (1990) Calcif. Tissue Int., 46, p. 20; Bagambisa, F.B., Joos, U., Schilli, W., (1993) J. Biomed. Mater. Res., 27, p. 1047; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., (1995) J. Biomed. Mater. Res., 29, p. 89; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , JAAS; Raemdonck, W., Ducheyne, P., Meester, P., (1984) Metal and Ceramic Materials, p. 143. , edited by P. Ducheyne and G. W. Hastings (CRC Press, Boca Raton, FL); Rey, C., Freche, M., Heughebaert, M., Vignoles, M., (1991) Bioceramics 4, p. 57. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner (Butterworth-Heinemann, London); Nagase, M., Abe, Y., Udagawa, E., (1992) Biomaterials, 13, p. 172; Burnie, J., Gilchrist, T., (1993) Ceramics in Surgery, p. 169. , edited by P. Vincenzini (Elsevier, Amsterdam); Burnie, F., Gilchrist, T., Ceramics in Surgery, p. 177; Rawlings, R.D., Rogers, P.S., Stokes, P.M., (1987) High Tech Ceramics, p. 73. , edited by P. Vincenzini (Elsevier, Amsterdam); Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Lakhan, J.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., (1995) J. Mater. Sci. Mater. Med., 6, p. 348; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., (1991) J. Biomed. Mater. Res., 25, p. 53; Jansen, J.A., Van Der Waerden, J.P.C.M., Wolke, J.G.C., (1993) J. Mater. Sci. Mater. Med., 4, p. 466; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1992) J. Biomed. Mater. Res., 26, p. 1365; Frayssinet, P., Tourenne, F., Rouquet, P., Conte, P., Delga, C., Bonel, G., (1994) J. Mater. Sci. Mater. Med., 5, p. 11; Lugscheider, E., Knepper, M., Heimberg, B., Dekker, A., Kirkpatrick, C.J., (1994) J. Mater. Sci. Mater. Med., 5, p. 371; Courteney-Harris, R.G., Kayser, M.V., Downes, S., (1995) Biomaterials, 16, p. 489; Labat, B., Chanson, A., Frey, J., (1995) J. Biomed. Mater. Res., 29, p. 1397; De Santis, D., Guerriero, C., Nocini, P.F., Ungersbock, A., Richards, G., Gotte, P., Armato, U., (1996) J. Mater. Sci. Mater. Med., 7, p. 21; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., (1997) J. Biomed. Mater. Res., 34, p. 247; Ong, J.L., Prince, C.W., Lucas, L.C., (1995) J. Biomed. Mater. Res., 29, p. 165; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., (1995) J. Mater. Sci. Mater. Med., 6, p. 144; Amédée, J., Bareille, R., Jeandot, R., Bordenave, L., Rémy, M., Rouais, F., Baquey, C., (1994) Biomaterials, 15, p. 1029; Maniatopoulos, C., Sodek, J., Melcher, A., (1988) Cell Tissue Res., 254, p. 317; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., (1990) J. Cell Phys., 143, p. 213; Gundle, R., Joyner, C.J., Triffit, J.T., (1995) Bone, 16, p. 597; Fernandes, M.H., Costa, M.A., Carvalho, G.S., (1997) J. Mater. Sci. Mater. Med., 8, p. 61; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1997) J. Mater. Sci. Mater. Med., 8, p. 233; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., (1996) J. Mater. Sci. Mater. Med., 7, p. 291; Morais, S., Dias, N., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., (1999) J. Biomed. Mater. Res., 44, p. 176; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Min., 14, p. 27; Ferraz, M.P., Monteiro, F.J., Santos, J.D., J. Biomed. Mater. Res., , submitted; Owen, T.A., Aronow, M., Shalhoub, V., (1990) J. Cell Phys., 143, p. 420; Martin, T.J., Findlay, D.M., Heath, J.K., Ng, K.W., (1993) Handbook of Experimental Pharmacology, p. 149. , edited by J. R. Mundy and T. J. Martin Berlin (Springer-Verlag); Stein, G.S., Lian, J.B., (1993) Cellular and Molecular Biology of Bone, p. 47. , edited by M. Noda (Academic Press, Tokyo); Anderson, H.C., Morris, D.C., (1993) Handbook of Experimental Pharmacology, p. 267. , edited by J. R. Mundy and T. J. Martin Berlin (Springer-Verlag); Gwynn, I.A.P., (1994) J. Mater. Sci. Mater. Med., 5, p. 357; Kirkpatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., (1997) J. Mater. Sci. Mater. Med., 8, p. 131; Legeros, R.Z., Orly, I., Gregoire, M., Daculsi, G., (1991) The Bone-Biomaterial Interface, p. 76. , edited by J. E. Davies (University of Toronto Press, Toronto); Chern Lin, J.H., Liu, M.L., Ju, C.P., (1994) J. Biomed. Mater. Res., 28, p. 723; Ghannam, E.L., Ducheyne, P., Spapiro, I., (1995) J. Biomed. Mater. Res., 29, p. 359; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 35; Radin, S.R., Ducheyne, P., (1993) J. Biomed. Mater. Res., 27, p. 1047; Best, S., Sim, B., Kayser, M., Downes, S., (1997) J. Mater. Sci. Mater. Med., 8, p. 97
Keywords: adult; alkaline phosphatase; article; Bone; bone marrow cell; Bone replacement materials; Calcium; calcium ion; case report; Cell culture; cell differentiation; cell growth; Cells; controlled study; culture medium; enzyme activity; Enzyme kinetics; glass; Growth kinetics; human; Human bone marrow cell; human cell; hydroxyapatite; male; osteoblast; Phosphates; phosphorus; priority journal; protein; protein determination; Proteins; scanning electron microscope; Scanning electron microscopy; Sprayed coatings

In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions - Morais, S.; Dias, N.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1999)
For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures. For periods up to 21 days human bone marrow was cultured in control conditions that favor the proliferation and differentiation of osteoblastic cells. The effect of AISI 316L corrosion products and the corresponding major separate metal ions (Fe, Cr, and Ni) were studied in three different phases of the culture period in order to investigate the effects of metal ions in cell populations representative of osteoblastic cells in different stages of differentiation. Toxicity consequences of the presence of metal ions in bone marrow cultures were evaluated by biochemical parameters (enzymatic reduction of MTT, alkaline phosphatase activity, and total protein content), histochemical assays (identification of ALP-positive cells and Ca and phosphates deposits), and observation of the cultures by light and scanning electron microscopy. Culture media were analyzed for total and ionized Ca and P and also for metal ions (Fe, Cr, and Ni). The presence of AISI 316L corrosion products and Ni salt in bone marrow cultures during the first and second weeks of culture significantly disturbs the normal behavior of these cultures, interfering in the lag phase and exponential phase of cell growth and ALP expression. However, the presence of these species during the third week of culture, when expression of osteoblastic functions occurs (mineralization process), did not result in any detectable effect. Fe salt also disturbs the behavior of bone marrow cell cultures when present during the lag phase and proliferation phase, and a somewhat compromised response between the normal pattern (control cultures) and intense inhibition (AISI 316L corrosion products and Ni salt-added cultures) was observed. Fe did not affect the progression of the mineralization phase. Osteogenic cultures exposed to Cr salt (Cr 3+) presented a pattern similar to the controls, indicating that this element does not interfere, in the concentration studied, in the osteoblastic differentiation of bone marrow cells. Quantification of metal ions in the culture media showed that Cr (originated from AISI 316L corrosion products but from not Cr 3+ salt) and Ni (originated from AISI 316L corrosion products and Ni salt) appear to be retained by the bone marrow cultures.
Cited By (since 1996): 35Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199902)44:2<176::AID-JBM8>3.0.CO;2-6PubMed ID: 10397919Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200 Porto, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Alloys; Biocompatible Materials; Calcium, 7440-70-2; Chromium, 7440-47-3; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Proteins; Stainless Steel, 12597-68-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1References: Williams, D., Cahn, R.W., Bever, M.B., (1990) Concise Encyclopedia of Medical & Dental Materials, pp. 4-70. , Oxford, New York, Beijing, Frankfurt, São Paulo, Sydney, Tokyo, Toronto: Permagon Press;Linden, J.V., Hopler, S.M., Gossling, H.R., Sunderman Jr., F.W., Blood nickel concentrations in patients with stainless-steel hip protheses (1985) Ann Clin Lab Sci, 15, pp. 459-464. , 1985; Weber, G.W., Reid, B.L., Nickel toxicity in young growing mice (1969) J Animal Sci, 28, pp. 620-623; O'Dell, G.D., Miller, W.J., King, W.A., Moore, S.L., Blackmon, D.M., Nickel toxicity in the young bovine (1970) J Nutrition, 100, pp. 1447-1453; Louria, D.B., Joselow, M.M., Browder, A.A., The human toxicity of certain trace elements (1972) Ann Intern Med, 76, pp. 307-319; Whanger, P.D., Effects of dietary nickel on enzyme activities and mineral contents in rats (1973) Toxicol Appl Pharmacol, 25, pp. 323-331; Woodman, J.L., Black, J., Jimenez, S., Organometallic corrosion products of 316L SS and HS-21 in serum: In vitro and in vivo comparison in an acute rat model (1982) Biomaterials 1980, pp. 245-253. , Winter GD, Gibbon DF, Plenk Jr H, editors. Chichester, New York, Brisbone, Toronto, Singapore: John Wiley & Sons; Parfitt, A.M., The physiological and clinical significance of bone histomorphometric data (1983) Bone Histomorphometry: Techniques and Interpretation, pp. 143-223. , Recker RR, editor. Boca Raton, Florida: CRC Press; Jilka, R.L., Manolagas, S.C., The cellular and biochemical basis of bone remodeling (1994) Osteoporosis, pp. 17-48. , Marcus R, editor. Boston: Blackwell Scientific Publications; Owen, M., Lineage of osteogenic cells and their relationship to the stromal system (1985) Bone and Mineral Research, 3, pp. 1-25. , Peck WA, editor. Amsterdam: Elsevier Science Publishers; Owen, T.A., Aronow, M., Shalhoub, V., Progressive development of the rat osteoblast phenotype in vitro: Reciprocal relationships in expression of genes associated with osteoblast proliferation and differentiation during formation of the bone extracellular matrix (1990) J Cell Physiol, 143, pp. 420-430; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized Ca in osteoblast-like cell culture medium (1996) Electroanalysis, 8 (12), pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9 (10), pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by catalytic cathodic stripping voltammetry with a mercury microelectrode (1998) J Trace Elements Med Biol, 2, pp. 101-108; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of Ni in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9 (5), pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 267-272; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tiss Res, 254, pp. 317-330; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): Subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch Biochem Biophys, 303, pp. 474-482; Bessey, O., Lowry, O., Breck, M., A method for the rapid determination of alkaline phosphatase with five cubic millileters of serum (1946) J Biol Chem, 164, pp. 321-326; McGee-Russell, M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Fiske, C.H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J Biol Chem, 66, pp. 373-400; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone and Miner, 8, pp. 239-250; Cheng, S.L., Yang, J.W., Riffas, L., Zhang, S.F., Avioli, L.V., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone-derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arcicla, C.R., Granchi, D.C., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin Mater, 15, pp. 173-190; Gerstenfeld, L.C., Chipman, S.D., Glowacki, J., Lian, J.B., Expression of differential function by mineralizing cultures of chicken osteoblasts (1987) Dev Biol, 122, pp. 46-60; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone and Miner, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone and Miner, 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Tokuoka, T., Shapiro, I.M., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif Tissue Int, 51, pp. 305-311; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone and Miner, 16, pp. 11-36; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Decreased consumption of Ca and P during in vitro biomineralization and biologically induced deposition of Ni and Cr in presence of stainless steel corrosion products (1998) J Biomed Mater Res, 42, pp. 199-212; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralization by osteoblast-like cells. 1. Retardation of tissue mineralization by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Effects of AISI 316L corrosion products in in vitro bone formation (1998) Biomaterials, 19, pp. 999-1007; Stein, G.S., Lian, J.B., Molecular mechanisms mediating developmental and hormone-regulated expression of genes in osteoblasts: An integrated relationship of cell growth and differentiation (1993) Cellular and Molecular Biology of Bone, pp. 47-95. , Noda M, editor. Tokyo: Academic Press Inc; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the one-hydroxyapatite interface in vitro (1992) J Biomed Mater Res, 26, pp. 1365-1382; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) Endocrin Rev, 4, pp. 290-297; Abe, Y., Akamine, A., Aida, Y., Maeda, K., Differentiation and mineralization in osteogenic precursor cells derived from fetal rat mandibular bone (1993) Calcif Tissue Int, 52, pp. 365-371; Lomri, A., Tran, M.P.V., Mott, M., Characterization of endosteal osteoblastic cells isolated from mouse caudal vertebrae (1988) Bone, 9, pp. 165-175; McCulloch, C.A.G., Fair, C.A., Tenebaum, H.C., Limeback, H., Homareau, R., Clonal distribution of osteoprogenitor cells in cultured chick peristoa: Functional relationship to bone formation (1990) Dev Biol, 140, pp. 352-361; Sun, Z.L., Wataha, J.C., Hanks, C.T., Effects of metal ions on osteoblast-like cell metabolism and differentiation (1997) J Biomed Mater Res, 34, pp. 29-37; Puleo, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Katz, S.A., Salem, H., The toxicology of Cr with respect to its chemical speciation: A review (1993) J Appl Toxicol, 13, pp. 217-224; Anderson, H.C., Morris, D.C., Mineralization (1993) Handbook of Experimental Pharmacology, pp. 267-298. , Mundy GR, Martin TJ, editors. Berlin: Springer-Verlag; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , Fraker AC, Griffin CD, editors. ASTM STP 859. Philadelphia: American Society for Testing and Materials; Rae, T., The toxicity of metals used in orthopaedic prostheses (1981) J Bone Joint Surg, 63 B, pp. 435-440; Webb, M., Weinzier, S.M., Uptake of 63Ni 2+ from its complexes with proteins and other ligands by mouse dermal fibroblasts in vitro (1972) Br J Cancer, 26, pp. 292-298; Merritt, K., Wortman, R.S., Millard, M., Brown, S.A., XPS analysis of 316LVM corroded in serum and saline (1983) Biomater Med Devices Artif Organs, 11, pp. 115-124; Bianchi, V., Toso, R.D., Debetto, P., Mechanisms of chromium toxicity in mammalian cell cultures (1980) Toxicology, 17, pp. 219-224; Lucas, L.C., Bearden, L.J., Lemons, J.E., Ultrastructural examination of in vitro and in vivo cells exposed to elements from type 316L stainless steel (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 208-222. , Fraker AC, Griffin CD, editors. ASTM STP 859. Philadelphia: American Society for Testing and Materials
Keywords: alkaline phosphatase; Alloys; article; Batch cell culture; Biocompatible Materials; biotechnology; Bone; Bone cells; bone marrow cell; Bone Marrow Cells; bone mineralization; bone prosthesis; Calcium; Cell culture; cell differentiation; Cell Division; cell population; Cells, Cultured; Chromium; controlled study; Corrosion; Corrosion products; Cytotoxicity; Differentiation; human; human cell; Human osteoblast-like cells; Humans; Implants (surgical); Ions; Iron; joint prosthesis; materials testing; metal ion; Metal ions; Metals; Nickel; osteoblast; Osteoblasts; phosphorus; Prostheses and Implants; Proteins; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles

Individual study of chromium in the stainless steel implants degradation: An experimental study in mice - Pereira, M.D.C.; Pereira, M.D.L.; Sousa, J.P. (BioMetalsBioMetals, 1999)
To study the accumulation and the histological effects in mice organs caused by hexavalent chromium, one of the corrosion products released from AISI 316L stainless steel implants, mice groups were subcutaneously injected with a metallic solution of chromium during a certain period of time. Similar injections were made with HBSS (Hank's Balanced Salt Solution) in other groups to be used as controls. The levels of chromium found in the liver, kidney and spleen of the control and the treated animals were obtained by atomic absorption spectrometry (AAS) and were compared to those obtained by AdSV (adsorptive stripping voltammetry) to test the accuracy of the results. During the experimental period, the liver and spleen showed a progressive and significant accumulation of chromium whereas in the kidney the significant accumulation found after the first week practically remained unchanged during the four weeks. Apparently, the histological analysis of these tissues did not evidence any relevant morphological alteration induced by the chromium accumulations during the four weeks of treatment.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: BOMEEPubMed ID: 10581692Language of Original Document: EnglishCorrespondence Address: Do Carmo Pereira, M.; Departamento de Engenharia Quimica, FEUP, Rua dos Bragas, 4050-123 Porto, Portugal; email: mcsp@fe.up.ptChemicals/CAS: Biocompatible Materials; Chromium, 7440-47-3; Stainless Steel, 12597-68-1References: Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8;Black, J., Maitin, E.C., Gelman, H., Morris, D.M., Serum concentrations of chromium, cobalt and nickel after total hip replacement: A six month study (1983) Biomaterials, 4, pp. 160-164; Brien, W.W., Salvati, E.A., Healey, J.H., Bansal, M., Ghelman, B., Betts, F., Osteogenic sarcoma arising in the area of a total hip replacement (1990) J Bone Joint Surg, 72 A, pp. 1097-1099; Brown, S.A., Farnsworth, U., Merritt, K., Crowe, T.D., In vitro and in vivo metal ion release (1988) J Biomed Mater Res, 22, pp. 321-338; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., In vivo transport and excretion of corrosion products from accelerated anodic corrosion of porous coaled 1-75 alloy (1993) J Biomed Mater Res, 27, pp. 1007-1017; Burrows, D., (1983) Chromium: Metabolism and Toxicity, , CRC Press, Boca Raton, Florida; Dobbs, H.S., Minski, M.J., Metal ion release after total hip replacement (1980) Biomaterials, 1, pp. 193-198; Kargacin, B., Squibb, K.S., Cosentino, S., Zhitkovich, A., Costa, M., Comparison of the uptake and distribution of chromate in rats and mice (1993) Biol Trace Element Res, 36, pp. 307-318; Katz, S.A., Salem, H., The toxicology of chromium with respect to its chemical speciation: A review (1993) J Appl Toxicol, 13, pp. 217-224; Katz, S.A., Salem, H., (1994) The Biological and Environmental Chemistry of Chromium, , VCH Publishers; Langard, S., Hensten-Pettersen, A., Chromium toxicology (1981) Systemic Aspects of Biocompatibility, p. 143. , Williams DF. eds. Boca Raton, Florida, CRC Press; Martin, A., Bauer, T.W., Manley, M.T., Marks, K.E., Osteosarcoma at the site of total hip replacement (1988) J Bone Joint Surg, 70 A, pp. 1561-1566; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , Fraker AC. Griffin CD. eds. Philadelphia, American Society for Testing and Materials; Merritt, K., Brown, S.A., Release of hexavalent chromium from corrosion of stainless steel and cobalt-chromium alloys (1995) J Biomed Mater Res, 29, pp. 627-633; Merritt, K., Brown, S.A., Sharkey, N.A., Blood distribution of nickel, cobalt, and chromium following intramuscular injection into hamsters (1984) J Biomed Mater Res, 18, pp. 991-1004; Merritt, K., Brown, S.A., Sharkey, N.A., The binding of metal salts and corrosion products to cells and proteins in vitro (1984) J Biomed Mater Res, 18, pp. 1005-1015; Merritt, K., Crowe, T.D., Brown, S.A., Elimination of nickel, cobalt, and chromium following repeated injections of high dose metal salts (1989) J Biomed Mater Res, 23, pp. 845-862; Merritt, K., Fedele, C.D., Brown, S.A., Chromium 6+ or 3+ release during corrosion; And in vivo distribution (1992) Biomaterial- Tissue Interfaces, Advances in Biomaterials, 10, pp. 49-53. , Doherty PJ. et al., eds; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using microelectrodes (1997) Electroanalysis, 9, pp. 150-154; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping voltammetric measurements of chromium accumulation in mice organs using mercury film microelectrodes (1997) Electroanalysis, 9, pp. 941-944; Pereira, M.C., Pereira, M.L., Sousa, J.P., Evaluation of nickel toxicity on liver, spleen and kidney of mice after administration of high-dose metal ion (1998) J Biomed Mater Res, 40, pp. 40-47; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping measurements of iron accumulation in mice kidney using microlectrodes and histological features (1998) J Trace Elements Med Biol, 12, pp. 50-55; Pohler, O.E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, pp. 158-228. , Rubin LR, ed. The C. V. Mosby Company; Ross, M.H., Rowrell, L.J., (1985) Histology a Text and Atlas, , Williams & Wilkins; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials; Second Symposium, pp. 223-247. , Fraker AC, Griffin CD, eds. American Philadelphia, Society for Testing and Materials; Sunderman F.W., Jr., Hopfer, S.M., Swift, T., Cohalt, chromium, and nickel concentrations in body fluids of patients with porous-coated knee or hip prostheses (1989) J Orthop Res, 7, pp. 307-315; Yang, J., Black, J., Competitive binding of chromium, cobalt and nickel to serum proteins (1994) Biomaterials, 15, pp. 262-268; Young, E., Houwing, R.H., Patch test results with standard allergens over a decade (1987) Contact Dermatitis, 17, pp. 104-107
Keywords: animal experiment; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; biomaterial; body weight; Chromium; controlled study; Corrosion; histology; histopathology; implant; Injections, Subcutaneous; Kidney; Liver; liver level; male; Mice; Mice organs; Mice, Inbred Strains; mouse; nonhuman; potentiometry; Prostheses and Implants; Spleen; Stainless steel; tissue distribution

Miniaturization and application of the MTT assay to evaluate metabolic activity of protozoa in the presence of toxicants - Dias, N.; Nicolau, A.; Carvalho, G.S.; Mota, M.; Lima, N. (Journal of Basic MicrobiologyJ. Basic Microbiol., 1999)
This paper describes a critical evaluation of a miniaturised colorimetric assay, using MTT (3-[4,5-dimethyl-thiazol-2-yl]-2,5-diphenyl-tetrazolium bromide) reduction, applied to protozoan viability testing. The toxic substances used were copper, zinc, Triton X-100 (a membrane surfactant) and cycloheximide (an inhibitor of the protein synthesis). The viability assay of the ciliate protozoan Tetrahymena pyriformis was optimised in terms of MTT concentration and incubation time. Since protozoa are non adherent cells the MTT assay was modified in order to maintain the medium in the well. MTT proved to be effective in the measurement of Tetrahymena pyriformis viability. Four hours of MTT incubation followed by 30 minutes of incubation with DMSO were found to be the best incubation times for optical density reading. Furthermore, 10 mg/ml of MTT solution was the concentration that gave higher values of optical densities with minor medium interference.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JBMIEdoi: 10.1002/(SICI)1521-4028(199905)39:2<103::AID-JOBM103>3.0.CO;2-DPubMed ID: 10335603Language of Original Document: EnglishCorrespondence Address: Lima, N.; Centro de Engenharia Biologica, Universidade do Minho, 4700 Braga, Portugal; email: nelson@iec.uminho.ptChemicals/CAS: Copper, 7440-50-8; Cycloheximide, 66-81-9; Octoxynol, 9002-93-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1; Zinc, 7440-66-6References: Berridge, M.V., Tan, S., Characterization of the cellular reduction of using 3-[4,5-dimethyl-thiazol-2-y1]-2,5-diphenyl-tetrazolium bromide-MTT: Subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch. Biochem. Biophysics, 303, pp. 474-482;Berridge, M.V., Tan, S., McCoy, K.D., Wang, R., The biochemical and cellular basis of cell proliferation assays that use tetrazolium salts (1996) Biochemica, 4, pp. 15-20; Carvalho, G.S., Castanheira, M., Diogo, I., Abreu, A.M., Sousa, J.P., Loon, J.A., Van Blitterswijk, C.A., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1996) J. Mat. Science: Mat. in Medicine, 7, pp. 77-83; Ciappeti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., In vitro evaluation of cell/biomaterial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Colgan, D.J., Spectrophotometric quantitation of DNA on blots after ethanol-solubilization of the MTT-formazan from anti-digoxigenin-based detection of nucleic acids (1993) Appl. Theor. Electrophoresis, 3, pp. 219-222; Cote, J., Kamen, A.A., Andre, G., Protein-free culture medium improvement. Testing additives and their interactive effects in 96-well plates (1993) Appl. Microb. Biotechnol., 39, pp. 577-584; Dias, N., Lima, N., Carvalho, G.S., Mota, M., Miniaturização do ensaio do MTT para avaliação da actividade metabólica dos protozoários (1997) Congresso Nacional de Microbiologia-MICRO' 97, , Tomar; Hanel, T., Gareis, M., Kollarczik, B., Citotoxicity of mycotoxins evaluated by the MTT-cell culture Assay (1994) Mycopathologia, 128, pp. 167-174; Lemieux, P., Michaud, M., Pagé, M., A new formazan amplified clonogenic assay for cytotoxicity testing (1993) Biotechnol. Techniques, 7, pp. 597-602; Martin, A., Clynes, C., Comparison of 5 microplate assays for in vitro cytotoxicity testing and cell proliferation assays (1993) Cytotechnology, 11, pp. 49-58; Mossman, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J. Immunol. Methods, 65, pp. 55-63; Roberts, Ch.T., Orias, E., A cycloheximide-resistant mutant of Tetrahymena pyriformis (1973) Exp. Cell Res., 81, pp. 312-316; Sasaki, C.Y., Passaniti, A., Identification of anti-invasive but noncytotoxic chemotherapeutic agents using the tetrazolium dye MTT to quantitative viable cells in matrigel (1998) Bio-techniques, 24, pp. 1038-1043; Stowe, R.P., Koenig, D.W., Mishra, S.K., Pierson, D.L., Non destructive and continuous spectrophotometric measurement of cell respiration using a tetrazolium-formazan microemulsion (1995) J. Microbiol. Methods, 22, pp. 283-292; Wilson, A.P., Citotoxicity and viability assays (1995) Animal Cell Culture - A Practical Approach. 2nd Ed., pp. 277-289. , (R. I. FRESHNEY, Editor). Oxford University Press, Oxford
Keywords: Animals; Ciliophora; Colorimetry; Copper; Cycloheximide; MTT assay; Octoxynol; Protozoa; Tetrahymena pyriformis; Tetrazolium Salts; Thiazoles; Zinc

Adhesion and microstructural characterization of plasma-sprayed hydroxyapatite/glass ceramic coatings onto Ti-6Al-4V substrates - Silva, P.L.; Santos, J.D.; Monteiro, F.J.; Knowles, J.C. (Surface and Coatings TechnologySurf. Coat. Technol., 1998)
Commercial hydroxyapatite (HA), Ca 10(PO 4) 6(OH) 2, powders were reinforced with 4% of a CaO-P 2O 5 based glass during its sintering process. Double layered coatings were obtained by Plasma Spraying and composed of 50 μm commercial HA, followed by a 50 μm (HA)/P 2O 5-CaO based glass composite coating. Samples were characterized by X-ray diffraction (XRD) analysis and it was shown that they were constituted of an HA matrix with small traces of tricalcium phosphate (β-TCP) phase. The XRD spectra were quite similar to those of commercial HA coatings. For coating to substrate adhesion two different tests were performed: adhesion tests according to ASTM C 633-79 and ASTM D 1002-83 standards. Higher values were obtained for ASTM C 633-79 than for ASTM D 1002-83, 35 and 15 MPa, respectively. This behavior is discussed in terms of the different stress effort applied to specimens. The results obtained with ASTM C 633-79 show that these double layered satisfy the stress requirements for load bearing biomedical applications. © 1998 Published by Elsevier Science S.A.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Silva, P.L.; INEB-Inst. de Engenharia Biomedica, Praça Coronel Pacheco 1, 4050 Porto, PortugalReferences: Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, p. 165. , Takayama Press System Center, JAAS, Tokyo;Barney, V.C., Levin, M.P., Adams, D.F., (1986) J. Periodont., 57, p. 764; Ducheyne, P., (1987) J. Biomed. Mater. Res. Appl. Biomater., 21, p. 219; Legeros, R.Z., (1988) Adv. Dent. Res., 2, p. 164; Williams, D., (1986) Medical and Dental Materials, , Pergamon Press; Akao, M., Haoki, K., Kato, (1981) J. Mater. Sci., 16, p. 809; With, G., Van Dijk, H., Hattu, N., Prijs, K., (1981) J. Mater. Sci., 16, p. 1592; Santos, J.D., Silva, P.L., Knowles, J.C., Monteiro, F.J., (1996) J. Mater. Sci. Mater. Med., 7, p. 187; Rey, C., (1990) Biomateriais, 11, p. 14; Evans, G., Behiri, J., Currey, J., Bonfield, B., (1990) J. Mater. Sci. Mater. Med., 1, p. 38; Matejka, D., Benko, B., (1989) Plasma Spraying of Metallic Materials, , Wiley, New York; Brown, S.D., (1984) Thin Sol. Films, 119, p. 127; Mittal, K.L., Adhesion Measurement of Thin Films, Thick Films and Bulk Coatings, , ASTM STP 840; ASTM D 1002, standard test method for strength properties of adhesive in shear by tension loading (1983) Annual Book of ASTM Standards; ASTM C 633-79, standard test method for adhesion or cohesive strength of flame sprayed coatings (1979) Annual Book of ASTM Standards Section 2; Ruiz, J., González, J.A., (1984) Rev. Metal., 20 (1). , Madrid
Keywords: Adhesion; Ceramic coatings; Characterization; coating; Hydroxyapatite glass ceramic coatings; materials testing; Mechanical properties; Microstructure; Phosphates; Plasma spraying; Stresses; Titanium aluminum vanadium substrates; X ray diffraction analysis; X-Ray Diffraction

Adsorptive stripping measurements of iron accumulation in mice kidney using microelectrodes and histological features - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 1998)
The toxic effects caused by iron in kidney was performed on experimental studies with mice following administration of a metallic solution of this specie to simulate the iron corrosion products of a metallic implant. To quantify the total levels of iron present in this organ, an electrochemical method was chosen based on the application of square wave voltammetry using adsorptive collection of iron-catechol on a mercury film microelectrode (MFM). The optimal working conditions to produce a very stable and reproducible iron peak in the digested kidney samples were found to be pH=7.2 provided by 8.0 mmol/L PIPES buffer, catechol concentration of 3.0x10
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JTEBFPubMed ID: 9638613Language of Original Document: EnglishCorrespondence Address: Sousa, J.P.; INEB-Inst. de Engenharia Biomedica, Departamento de Engenharia Quimica, Faculdade Engenharia Univ. do Porto, Praca do Coronel Pacheco, 1, 4050 Porto, PortugalChemicals/CAS: Iron, 7439-89-6; Mercury, 7439-97-6References: Traisnel, M., Le Maguer, D., Hildebrand, H.F., Iost, A., Corrosion of surgical implants (1990) Clin. Mater., 5, pp. 309-318;Sutow, E.J., Pollack, S.R., The biocompatibility of certain stainless steels (1981) Biocompatibility of Clinical Implant Materials, 1, pp. 77-98. , Williams, D.F. eds CRC Press, Boca Raton, Florida; Ferguson Jr., A.B., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J. Bone Joint Surg., 42 A, pp. 77-90; Winter, G.D., Wear and corrosion products in tissues and the reactions they provoke (1976) Biocompatibility of Implant Materials, pp. 28-54. , Williams, D.F. eds London; Lux, F., Zeisler, R., Investigations of the corrosive deposition of components of metal implants and the behaviour of biological trace elements in metallosis tissue by means of instrumental multi-element activation analysis (1974) J. Radioanal. Chem., 19, pp. 289-297; Merritt, K., Brown, S.A., Sharkey, N.A., Blood distribution of nickel, cobalt, and chromium following intramuscular injection into hamsters (1984) J. Biomed. Mater. Res., 18, pp. 991-1004; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , Fraker, A.C., Griffin, C.D. eds American Society for Testing and Materials, Philadelphia; K. Merritt, K.A., Brown, S.A., Metal sensitivity reactions to bone screws in rabbits (1982) Clinical Applications of Biomaterials, pp. 85-93. , John Wiley & Sons Ltd; Woodman, J.L., Black, J., Jimenez, S., Organometallic corrosion products of 316L SS HS-21 in serum: In vitro and in vivo comparison in an acute rat model (1982) Biomaterials 1980, pp. 245-250. , Winter, G.D., Gibbons, D.F., Plenk, Jr., H. John Wiley & Sons Ltd; Merritt, K., Crowe, T.D., Brown, S.A., Elimination of nickel, cobalt, and chromium following repeated injections of high dose metal salts (1989) J. Biomed. Mater. Res., 23, pp. 845-862; Pereira, M.L., Pereira, M.C., Sousa, J.P., Evaluation of nickel effects on mouse liver: Tissue response and metal ion accumulation (1995) Biomedical Letters, 52, pp. 235-244; Pereira, M.C., Pereira, M.L., Sousa, J.P., Evaluation of nickel toxicity on liver, spleen and kidney of mice after administration of high-dose metal ion (1997) J. Biomed. Mater Res., pp. XXXXXX. , in press; Schafer, B.A.I., Cheron, R.G., Dluhy, R., Cooper, B., Gleason, R.E., Soeldner, J.S., Bunn, H.F., Clinical consequences of acquired transfusional iron overload in adults (1981) N Engl. J. Med., 304, p. 319; Black, J., Mineral metabolism (1981) Biological Performance of Materials: Fundamentals of Biocompatibility. Biomedical Engineerins and Instrumentation Series, pp. 158-168. , Plonsey R., Katz, J.L. Marcel Dekker; Bernat, I., Iron deficiency (1983) Iron Metabolism, pp. 215-274. , Plenum Press, New York; Nakamura, K., Watanabe, H., Orii, H., Direct measurement of iron in serum by electrothermal atomic absorption spectrometry (1980) Anal. Chim. Acta., 108, pp. 67-71; Van Beek, H., Greefkes, H.C.A., Baars, A.J., Determination of copper, iron, manganese, lead and cadmium in automatically wet-digested animal tissue by graphite-furnace atomic absorption spectrometry with Zeeman background correction (1993) Talanta., 34, pp. 580-582; Van Wyck, D.B., Schifman, R.B., Stivelman, J.C., Ruiz, J., Martin, D., Rapide sample preparation for determination of iron in tissue by closed-vessel digestion and microwave energy (1988) Clin. Chem., 34 (6), pp. 1128-1130; Chakraborti, D., Burguera, M., Burguera, J.L., Analysis of standard reference materials after microwave-oven digestion in open vessels using graphite furnace atomic absorption spectrophotometry and Zeeman-effect background correction (1993) Fresenius J. Anal. Chem., 347, pp. 233-237; Lugowski, S., Smith, D.C., Van Loon, J.C., The determination of At, Cr, Co, Fe, and Ni in whole blood by electrothermal atomic absorption spectrophotometry (1987) J. Biomed. Mater. Res., 21, pp. 657-674; Wightman, R.M., Microvoltammetric electrodes (1981) Anal. Chem., 53, pp. 1125A-1134A; Pletcher, D., Why microelectrodes? (1991) Microelectrodes: Theory and Applications, pp. 3-16. , Montenegro, M.I., Queirós, M.A., Daschbach, J.L eds NATO-ASI, Kluwer Academic Publishers, the Netherlands; Wojciechowski, M., Go, W., Osteryoung, J., Square-wave anodic stripping analysis in the presence of dissolved oxygen (1984) Anal. Chem., 57, pp. 155-158; Kalvoda, R., Kopanica, M., (1989) Pure & Appl. Chem., 61, pp. 97-112; Wang, J., Principles (1985) Stripping Analysis, pp. 9-64. , VCH publishers, Inc; Perejra, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using mercury microelectrodes (1996) Electroanalysis, 9, pp. 150-154; Van Den Berg, C.M.G., Huang, Z.Q., Determination of iron in seawater using cathodic stripping voltammetry preceded by adsorptive collection with the hanging mercury drop electrode (1984) J. Electroanal. Chem., 177, pp. 269-280; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell cultures medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9; Wang, J., Mannino, S., Application of adsorptive stripping voltammetry to the speciation and determination of iron (III) and total iron in wines (1989) Analyst, 114, pp. 643-645; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 223-247. , Fraker, A.C. and Griffin. Eds. American Society for Testing Materials; Pereira, M.C., Sousa, J.P., Determination of total iron in biological sample solutions with mercury microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 273-278; Pereira, M.C., Pereira, M.L., Sousa, J.P., Adsorptive stripping voltammetric measurements of chromium accumulation in mice organs using mercury microelectrodes (1997) Electroanalysis, 9, pp. 941-944
Keywords: , biomaterials; Adsorptive stripping; animal experiment; animal model; animal tissue; Animals; article; atomic absorption spectrometry; biomaterial; controlled study; electrochemical analysis; electrochemistry; histology; Iron; iron absorption; Kidney; male; Mercury; metal implantation; Mice; microelectrode; Microelectrodes; mouse; nonhuman; potentiometry; priority journal; Toxicology

Chromium determination in osteoblast-like cell culture medium by catalytic cathodic stripping voltammetry with a mercury microelectrode - Morais, S.; De Carvalho, G.S.; Sousa, J.P. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 1998)
A catalytic cathodic stripping voltammetric procedure for the determination of total chromium in osteoblast-like cell culture medium using a mercury film microelectrode (MFM) was optimised. The method is based on the pre-concentration of the Cr(III)-diethylenetriaminepentaacetic acid (DTPA) complex by adsorption at the potential of -1.00 V (vs. Ag/AgCl) in the presence of 10 x 10
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JTEBFPubMed ID: 9760419Language of Original Document: EnglishCorrespondence Address: Morais, S.; Inst. Engenharia Biomedica (INEB), Praca Coronel Pacheo 1, 4050 Porto, PortugalChemicals/CAS: Acetates; Chromium, 7440-47-3; Culture Media; Mercury, 7439-97-6; NitratesReferences: Ferguson Jr., A.B., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J. Bone Joint Surg., 42 A, pp. 77-90;Ferguson Jr., A.B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Trace metal ion concentration in the liver, kidney, spleen and lung of normal rabbits (1962) J Bone Joint Surg., 44 A, pp. 317-322; Ferguson Jr., A.B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Characteristics of trace ions released from embedded metal implants in the rabbit (1962) J. Bone Joint Surg. 1962, 44 A, pp. 323-336; Lux, F., Ziesler, R., Investigations of the corrosive deposition of components of metal implants and of the behaviour of biological trace elements in metallosis tissue by means of instrumental multi-elemental activation analysis (1974) J. Radioanal. Chem., 19, pp. 289-297; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 223-247. , ASTM STP 859 (Fraker, A. C. and Griffin, C. D. ,Eds.). American Society for Testing and Materials, Philadelphia; Minski, M.J., Dobbs, H.S., (1980) Trace Element Analytical Chemistry in Medicine and Biology, pp. 339-350. , Bratter, P., Schramel, P., Eds., Walter de Gruyter, Berlin; Smith, G.K., (1982) Systemic Transport and Distribution of Iron and Chromium from 316L Stainless Steel Implants, , Ph.D. Thesis, University of Pennsylvania, Philadelphia; Brown, S.A., Farnsworth, L.J., Merritt, K., Crowe, T.D., In vitro and in vivo metal ion release (1988) J. Biomed. Materials Research, 22, pp. 321-338; Lucas, L.C., Bearden, L.J., Lemons, J.E., Ultrastructural examination of in vitro and in vivo cells exposed to elements from type 316L stainless steel (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 208-222. , ASTM STP 859 (Fraker, A. C. and Griffin, C. D., Eds.), American Society for Testing and Materials, Philadelphia; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, pp. 195-207. , ASTM STP859 (Fraker, A. C. and Griffin, C. D., Eds.), American Society for Testing and Materials, Philadelphia; Smith, G.K., Black, J., Models for systemic effects of metallic implants (1977) NBS Special Publication 472, pp. 23-28. , Weinstein, A., Eds., U. S. Government Printing Office, Washington D. C; Deutman, R., Mulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J. Bone Jt. Surg., 59 A, pp. 862-865; Crosmun, S.T., Mueller, T.R., The determination of chromium (VI) in natural waters by differential pulse polarography (1975) Anal. Chim. Acta, 75, pp. 199-205; Golimowski, J., Valenta, P., Nurnberg, H.W., Trace determination of chromium in various water types by adsorption differential pulse polarography (1985) Fresenius Z. Anal. Chem., 322, pp. 315-322; Boussemart, M., Van Den Berg, C.M.G., Ghaddaf, M., The determination of the chromium speciation in sea water using catalytic cathodic stripping voltammetry (1992) Anal. Chim. Acta, 262, pp. 103-115; Paneli, M., Voulgaropoulos, A.V., Kalcher, K., The catalytic adsorptive stripping voltammetry determination of chromium with TTHA and nitrate (1993) Mikrochim. Acta, 110, pp. 205-215; Wang, J., Lu, J.A., Olsen, K., Measurement of ultratrace levels of chromium by adsorptive-catalytic stripping voltammetry in the presence of cupferron (1992) Analyst, 117, pp. 1913-1917; Nurnberg, H.W., Studies on toxic trace metals in the environment by advanced polarographic methods (1978) Proc. Analyt. Div. Chem. Soc., 15, pp. 275-283; Ottaway, J.M., Fell, G.S., Determination of chromium in biological materials (1986) Pure and Applied Chemistry, 58, pp. 1707-1720; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionised calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part I- Retardation of tissue mineralisation by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., Bruijn, J.D., Van Blitterswijk, C.A., Decreased consumption of Ca and P during in vitro biomineralisation and biologically-induced deposition of Ni and Cr in the presence of stainless steel corrosion products (1998) J. Biomed. Mater. Res., , in press; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro osteoblastic differentiation of human bone marrow cells in the presence of metal ions (1998) J. Biomed. Mater. Res., , in press; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res., 254, pp. 317-330; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, M., Tolg, G., Wet mineralisation of organic matrices in glassy carbon vessels in a pressure-bomb system for trace element analysis (1979) Talanta, 26, pp. 681-691; Peng, J., Jin, W., Anodic stripping voltammetric determination of trace lead in micro-samples with a mercury-ultramicroelectrode (1992) Anal. Chim. Acta, 264, pp. 213-219; Wehmeyer, K.R., Wightman, R.M., Cyclic voltammetry and anodic stripping voltammetry with mercury ultramicroelectrodes (1985) Anal. Chem., 57, pp. 1989-1993; Wightman, R.M., Wiptd, O., Voltammetry at ultramicroelectrodes (1989) Electroanalytical Chemistry, 15, pp. 335-336. , Bard, A. J., Ed., Marcel, Dekker, New York; Wurfels, M., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid Part 3 a (1989) Anal. Chim. Acta, 226, pp. 31-41; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part II- Characterisation of cellular culture supernatants (1998) Biomaterials, 19, pp. 23-29; Wurfels, M., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid Part 2 a (1989) Anal. Chim. Acta, 226, pp. 17-30; Gilbert, T.R., Clay, A.M., Determination of chromium in sea water by atomic absorption spectrometry (1973) Anal. Chim. Acta, 67, pp. 289-295; Ping, L., Matsumoto, K., Fuwa, K., Determination of urinary chromium levels for healthy men and diabetic patients by electric thermal atomic absorption spectrometry (1983) Anal. Chim. Acta, 147, pp. 205-212; Torrance, K., Gatford, C., Determination of soluble chromium in simulated PWR coolant by differential-pulse adsorptive stripping voltammetry (1987) Talanta, 34, pp. 939-944; Lanza, P., Taddia, M., The differential pulse polarographic determination of chromium in gallium arsenide (1984) Anal. Chim. Acta, 157, pp. 37-44; Miller, J.N., Basic statistical methods for analytical chemistry. Part 2: Calibration and regression (1991) Analyst, 116, pp. 3-14; Ringbom, A., (1963) Complexation in Analytical Chemistry, pp. 332-333. , Elving, P. J. and Kolthoff, I. M., Eds, Interscience Publishers, New York/London; Black, J., Maitin, E.C., Gelman, H., Morris, D.M., Serum concentrations of Cr, Co, and Ni after total hip replacement: A six months study (1983) Biomaterials, 4, pp. 160-164; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dobbs, H.S., Minski, J., Metal ion release after total hip replacement (1980) Biomaterials, 1, pp. 193-198; Katz, S., Salem, H., The toxicology of chromium with respect to its speciation: A review (1993) J. Applied Toxicology, 13, pp. 217-224; Bianchi, V., Toso, R.D., Debetto, P., Mechanisms of chromium toxicity in mammalian cell cultures (1980) Toxicology, 17, pp. 219-224; Hopkins, L.L., Schwartz, K., Chromium (III) binding to serum proteins, specifically siderophilin (1964) Biochem. Biophys. Acta, 90, pp. 484-491; Nurnberg, H.W., The voltammetric approach in trace metal chemistry of natural waters and atmospheric precipitation (1984) Anal. Chim. Acta, 164, pp. 1-21
Keywords: Acetates; animal cell; Animalia; Animals; article; atomic absorption spectrometry; Bone Marrow Cells; catalysis; Cell culture; Cells, Cultured; Chromium; complex formation; controlled study; Culture Media; culture medium; drug determination; electrochemistry; Electrodes; Hydrogen-Ion Concentration; in vitro study; Kinetics; Mercury; microelectrode; Microelectrodes; Nitrates; nonhuman; osteoblast; Osteoblasts; potentiometry; priority journal; Rabbits; Reproducibility of Results; sensitivity and specificity; Stromal Cells; technique

Classification of foetal heart rate sequences based on fractal features - Felgueiras, C.S.; De Marques Sá, J.P.; Bernardes, J.; Gama, S. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 1998)
Visual inspection of foetal heart rate (FHR) sequences is an important means of foetal well-being evaluation. The application of fractal features for classifying physiologically relevant FHR sequence patterns is reported. The use of fractal features is motivated by the difficulties exhibited by traditional classification schemes to discriminate some classes of FHR sequence and by the recognition that this type of signal exhibits features on different scales of observation, just as fractal signals do. To characterise the signals by fractal features, two approaches are taken. The first models the FHR sequences as temporal fractals. The second uses techniques from the chaos-theory field and aims to model the attractor based on FHR sequences. The fractal features determined by both approaches are used to design a Bayesian classification scheme. Classification results for three classes are presented; they are quite satisfactory and illustrate the importance of this type of methodology.Visual inspection of foetal heart rate (FHR) sequences is an important means of foetal well-being evaluation. The application of fractal features for classifying physiologically relevant FHR sequence patterns is reported. The use of fractal features is motivated by the difficulties exhibited by traditional classification schemes to discriminate some classes of FHR sequence and by the recognition that this type of signal exhibits features on different scales of observation, just as fractal signals do. To characterise the signals by fractal features, two approaches are taken. The first models the FHR sequences as temporal fractals. The second uses techniques from the chaos-theory field and aims to model the attractor based on FHR sequences. The fractal features determined by both approaches are used to design a Bayesian classification scheme. Classification results for three classes are presented; they are quite satisfactory and illustrate the importance of this type of methodology.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: MBECDdoi: 10.1007/BF02510743PubMed ID: 9684460Language of Original Document: EnglishCorrespondence Address: Felguiras, C.S.; Instituto de Engenharia Biomedica, Praca Coronel Pacheco 1, 4050 Porto, PortugalReferences: Bernardes, J., (1993) Leitura Automatizada Do Cardiotocograma. Desenvolvimento e Availiaçào, , Ph.D. thesis, Faculdade de Medicina da Universidade do Porto, Portugal;Bernardes, J., Moura, C., Marques De Sá, J.P., Pereira Leite, L., Van Geijn, H.P., The Porto system (1994) A Critical Appraisal of Foetal Surveillance, pp. 315-324. , VAN GEIJN H. P. and COPRAY, F. J. A. (Eds.) Elsevier Science, Amsterdam; Chaffin, D.G., Goldberg, C.C., Reed, K.L., The dimension of chaos in foetal heart rate (1991) Am. J. Obstet. Gynecol., 165 (5), pp. 1425-1429; Dawes, G.S., Visser, G.H.A., Goodman, J.D.S., Redman, C.W.G., Numerical analysis of human foetal heart rate: The quality of ultrasound records (1981) Am. J. Obstet, Gynecol., 141 (1), pp. 43-52; Felgueiras, C.S., Marques De Sá, J.P., Bernardes, J., Gama, S., On the reconstruction of foetal heart rate sequences (1996) Actas de Bieng '96, Sociedade Portuguesa de Engenharia Biomédica, Aveiro, Março, 1996, pp. VII61-VII65; Goldberger, A.L., Fractal mechanisms in the electrophysiology of the heart (1992) IEEE Eng. Med. Biol., pp. 47-52. , June; Grant, A., Principles for clinical evaluation of methods of perinatal monitoring (1984) J. Perinat. Med., 12, pp. 227-231; Grassberger, P., Procaccia, I., Measuring the strangeness of strange attractors (1983) Physica D, 9, pp. 189-208; Higushi, T., Approach to an irregular time series on the basis of the fractal theory (1988) Physica D, 31, pp. 277-283; Hoyer, D., Liebovitch, L.S., Schmidt, K., Luethke, B., Zwiener, U., Practical problems of determining the dimensions of heart rate data (1997) Med. Biol. Eng. Comput., 35, pp. 27-32; Maldelbrot, B.B., Van Ness, J.W., Fractional Brownian motions, fractional noises and applications (1968) SIAM Rev., 10 (4), pp. 422-437; Marques De Sa, J.P., Moura, A.C., Bernardes, J., Pereira Leite, L., Análise automática de sinais cardiotocográficos (1992) Acta Médica Portuguesa 11 Série, 5 (1), pp. 28-30; Parker, T.S., Chua, L.O., (1989) Practical Numerical Algorithms for Chaotic Systems, , Springer-Verlag; Schulman, H., Schulman, S., Lai, P., Schneider, E., Farmakides, G., Dawes, G., Antepartum computerized foetal heart rate, chaos analysis, blood gases and perinatal outcome (1994) J. Maternal-Fetal Invest., 4, pp. 59-63
Keywords: article; Bayes Theorem; Cardiology; Chaos techniques; Chaos theory; Classification; Computer aided analysis; Computer simulation; Electrocardiography; Female; Fetal monitoring; fetus; fetus heart rate; FHR classification; FHR sequence; Foetal heart rate sequences; fractal analysis; Fractal features; Fractals; Heart Rate, Fetal; human; Humans; Pattern recognition; Pregnancy; Signal Processing, Computer-Assisted; technique

Decreased consumption of Ca and P during in vitro biomineralization and biologically induced deposition of Ni and Cr in presence of stainless steel corrosion products - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S.; De Bruijn, J.D.; Van Blitterswijk, C.A. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
The purpose of this study was to investigate the effects of 316L stainless steel (SS) corrosion products on the in vitro biomineralization process, because tissue necrosis, bone loss, impaired bone mineralization, and loosening of orthopedic implants are associated with ions and debris resulting from biodegradation. Rat bone marrow cells were cultured in experimental conditions that favored the proliferation and differentiation of osteoblastic cells and were exposed to SS corrosion products obtained by electrochemical means for periods ranging from 1 to 21 days. Quantification of total and ionized Ca and P, as well as Fe, Cr, and Ni, ions in the culture media of control and metal added cultures during the incubation period was performed to study the influence of corrosion products on the Ca and P consumption that occurs during the mineralization process. Control cultures and metal effects on cultures were evaluated concerning DNA content, enzymatic reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and alkaline phosphatase (ALP) activity. Histochemical detection of ALP, Ca, and phosphate deposition, and examination of the cultures by scanning and transmission electron microscopy (SEM and TEM) were also performed. The presence of SS corrosion products resulted in impairment of the normal behavior of rat bone marrow cultures. Levels of Cr and Ni in the medium of cultures exposed to 316L SS corrosion products decreased throughout the incubation period, suggesting a regular deposition of these species; these results were supported by TEM observation of the cultures. Cultures exposed to the corrosion products presented lower DNA content, MTT reduction, and ALP activity and failed to form mineralized areas. These cultures showed negative staining on histochemical reactions for the identification of calcium and phosphate deposition and SEM and TEM examination did not show mineral globular structures or mineralization foci, respectively, which is characteristic of cultures grown in control conditions. These results suggest that metal ions associated with 316L SS are toxic to osteogenic cells, affecting their proliferation and differentiation.The purpose of this study was to investigate the effects of 316L stainless steel (SS) corrosion products on the in vitro biomineralization process, because tissue necrosis, bone loss, impaired bone mineralization, and loosening of orthopedic implants are associated with ions and debris resulting from biodegradation. Rat bone marrow cells were cultured in experimental conditions that favored the proliferation and differentiation of osteoblastic cells and were exposed to SS corrosion products obtained by electrochemical means for periods ranging from 1 to 21 days. Quantification of total and ionized Ca and P, as well as Fe, Cr, and Ni, ions in the culture media of control and metal added cultures during the incubation period was performed to study the influence of corrosion products on the Ca and P consumption that occurs during the mineralization process. Control cultures and metal effects on cultures were evaluated concerning DNA content, enzymatic reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and alkaline phosphatase (ALP) activity. Histochemical detection of ALP, Ca, and phosphate deposition, and examination of the cultures by scanning and transmission electron microscopy (SEM and TEM) were also performed. The presence of SS corrosion products resulted in impairment of the normal behavior of rat bone marrow cultures. Levels of Cr and Ni in the medium of cultures exposed to 316L SS corrosion products decreased throughout the incubation period, suggesting a regular deposition of these species; these results were supported by TEM observation of the cultures. Cultures exposed to the corrosion products presented lower DNA content, MTT reduction, and ALP activity and failed to form mineralized areas. These cultures showed negative staining on histochemical reactions for the identification of calcium and phosphate deposition and SEM and TEM examination did not show mineral globular structures or mineralization foci, respectively, which is characteristic of cultures grown in control conditions. These results suggest that metal ions associated with 316L SS are toxic to osteogenic cells, affecting their proliferation and differentiation.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199811)42:2<199::AID-JBM5>3.0.CO;2-KPubMed ID: 9773816Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Manuel Pereira da Silva, 4200 Porto, PortugalChemicals/CAS: Biocompatible Materials; Calcium, 7440-70-2; Chromium, 7440-47-3; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Steel, 12597-69-2References: Ferguson Jr., B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Trace metal ion concentration in the liver, kidney, spleen and lung of normal rabbits (1962) J. Bone Joint Surg., 44 A, pp. 317-322;Ferguson Jr., A.B., Akahoshi, Y., Laing, P.G., Hodge, E.S., Characteristics of trace ions released from embedded metal implants in the rabbit (1962) J. Bone Joint Surg., 44 A, pp. 323-336; Ferguson Jr., A.B., Laing, P.G., Hodge, E.S., The ionization of metal implants in living tissues (1960) J. Bone Joint Surg., 42 A, pp. 77-90; Lux, F., Ziesler, R., Investigations of the corrosive deposition of components of metal implants and of the behavior of biological trace elements in metallosis tissue by means of instrumental multi-elemental activation analysis (1974) J. Radioanal. Chem., 19, pp. 289-297; Smith, G.K., Black, J., Estimation of in vivo type 316L stainless steel corrosion rate from blood transport and organ accumulation data (1985) Corrosion and Degradation of Implant Materials: Second Symposium, ASTM STP 859, pp. 223-247. , A. C. Fraker and C. D. Griffin (eds.), American Society for Testing and Materials, Philadelphia, Pennsylvania; Merritt, K., Brown, S.A., Biological effects of corrosion products from metals (1985) Corrosion and Degradation of Implant Materials: Second Symposium, ASTM STP 859, pp. 195-207. , A. C. Fraker and C. D. Griffin, (eds.), American Society for Testing and Materials, Philadelphia, Pennsylvania; Smith, G.K., Black, J., Models for systemic effects of corrosion products (1977) Retrieval and Analysis of Orthopedics Implants, pp. 23-28. , A. Weinstein D. Gibbons, S. A. Brown, and A. W. Ruff (eds.), NBS Special Publication 472, U.S. Government Printing Office, Washington, D.C; Deutman, R., Mulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J. Bone Joint Surg., 59 A, pp. 862-865; Verne, J., Sannie, C., Etude de l'action toxique des cations sur les fibroblastes cultivés in vitro (1933) Compt. Rend. Acad. Sci., 196, pp. 1246-1247; Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regul. Affairs, 4, pp. 13-22; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J. Mater. Sci. Mater. Med., 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J. Mater. Sci. Mater. Med., 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , P. J. Doherty et al. (eds.), Amsterdam, Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Abreu, A.M., Sousa, J.P., Loon, J.A., Blitterswijk, C.A., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J. Mater. Sci. Mater. Med., 7, pp. 77-83; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J. Bone Joint Surg., 56 B, pp. 626-642; Betts, F., Wright, T., Salvati, E.A., Boskey, A., Mansal, M., Cobalt alloy metal debris in periarticular tissues from total hip revision arthoplasties (1992) Clin. Orthop., 278, pp. 75-82; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralization by osteoblast-like cells: Part 1-Retardation of tissue mineralization by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Electrochemical characterization of iron species in osteoblast-like cell culture medium (1995) Port. Electrochim. Acta, 13, pp. 483-487; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9, pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Port. Electrochim. Acta, 14, pp. 267-272; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode J. Trace Elements Med. Biol., , in press; Nurnberg, H.W., The voltammetric approach in trace metal chemistry of natural waters and atmospheric precipitation (1984) Anal.Chim. Acta, 164, pp. 1-21; Merritt, K., Wortman, R.S., Millard, M., Brown, S.A., XPS analysis of 316 LVM corroded in serum and in saline (1983) Biomater. Med. Devices Artif. Org., 11, pp. 115-127; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res., 254, pp. 317-330; Fiske, H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J. Biol. Chem., 66, pp. 373-400; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., Histological and biochemical evaluation of osteoblasts cultured on bioactive glass, hydroxylapatite, titanium alloy, and stainless steel (1993) J. Biomed. Mater. Res., 27, pp. 465-475; Bessey, O.A., Lowry, O.H., Breck, M.J., A method for the rapid determination of alkaline phosphatase with five cubic millimeters of serum (1946) J. Biol. Chem., 164, pp. 321-326; Karster, U., Wollenberger, A., Improvements in the ethidium bromide method for direct fluorometric estimation of DNA and RNA in cell and tissue homogenates (1977) Anal. Biochem., 77, pp. 464-470; McGee-Russell, S.M., Histochemical methods for calcium (1958) J. Histochem. Cytochem., 6, pp. 22-42; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulte formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Tassinari, M.S., Stein, G.S., Lian, J.B., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J. Cell Physiol., 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone Miner., 8, pp. 239-250; Cheng, S.L., Yang, J.W., Rifas, L., Zhang, S.F., Avioli, L.V., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Berridge, V., Tan, A.S., Characterization of the cellular reduction of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT): Subcellular localization, substrate dependence, and involvement of mitochondrial electron transport in MTT reduction (1993) Arch. Biochem. Biophys, 303, pp. 474-482; Ciapetti, G., Cenni, E., Stea, S., Pizzoferrato, A., In vitro evaluation of cell/biomaterial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Sgouras, D., Duncan, R., Methods for the evaluation of biocompatibility of soluble synthetic polymers which have potential for biomedical use: 1-Use of the tetrazolium-based colorimetric assay (MTT) as a preliminary screen for evaluation of in vitro cytotoxicity (1990) J. Mater. Sci. Mater. Med., 1, pp. 61-68; Martin, A., Clynes, M., Comparison of 5 microplate colorimetric assays for in vitro cytotoxicity testing and cell proliferation assays (1993) Cytotechnology, 11, pp. 49-58; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) Endosc. Rev., 4, pp. 290-297; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., The ultradtructure of the bone hydroxyapatite interface in vitro (1992) J. Biomed, Mater. Res., 26, pp. 1365-1382; Davies, J.E., Chernecky, R., Lowenberg, B., Shiga, A., Deposition and resorption of calcified matrix in vitro by rat marrow cells (1991) Cells Mater., 1, pp. 3-15; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., De Bruijn, J.D., Van Blitterswijk, C.A., Effects of AISI 316L corrosion products in in vitro bone formation (1998) Biomaterials, 19, pp. 999-1007; Pohler, E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, pp. 158-228. , L. R. Rubin (ed.), C. V. Mosby, St. Louis, Missouri; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Miner., 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Miner., 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Tokuoka, T., Shapiro, I.M., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif. Tissue Int., 51, pp. 305-311; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone Miner., 16, pp. 11-36; Rae, T., The toxicity of metals used in orthopaedic prostheses (1981) J. Bone Joint Surg., 63 B, pp. 435-440; Webb, M., Weinzierl, S.M., Uptake of 63Ni 2+ from its complexes with proteins and other ligands by mouse dermal fibroblasts in vitro (1972) Br. J. Cancer, 26, pp. 292-298; Katz, S.A., Salem, H., The toxicology of chromium with respect to its speciation: A review (1993) J. Appl.Toxicol., 13, pp. 217-224; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J. Appl. Biomater., 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J. Appl. Biomater., 6, pp. 249-258
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; alkaline phosphatase; animal cell; Animal cell culture; Animals; article; Biocompatible Materials; Biodegradation; biomineralization; Bioprosthesis; Bone; Bone and Bones; bone atrophy; bone marrow; Calcification, Physiologic; Calcium; calcium ion; Catalyst activity; Cells, Cultured; Chromium; controlled study; Corrosion; Corrosion products; Enzymes; Implants (surgical); metal implantation; mineralization; Nickel; nonhuman; osteoblast; Osteoblast-like cells; phosphate; phosphorus; prosthesis loosening; rat; Rats; Scanning electron microscopy; Stainless steel; Stainless steel corrosion products; Steel; Steel corrosion; tissue necrosis; transmission electron microscopy

Effects of AISI 316L corrosion products in in vitro bone formation - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S.; De Bruijn, J.D.; Van Blitterswijk, C.A. (BiomaterialsBiomaterials, 1998)
Rat bone marrow cells were cultured in experimental conditions that favour the proliferation and differentiation of osteoblastic cells (i.e., 2.52 x 10
Cited By (since 1996): 38Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00234-2PubMed ID: 9692798Language of Original Document: EnglishCorrespondence Address: Morais, S.; Universidade do Porto, Porto, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium Phosphates; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Stainless Steel, 12597-68-1References: Spector, M., Cease, C., Tong-Li, X., The local tissue response to biomaterials (1989) Crit Rev Biocompat, 5, pp. 269-295;Van Blitterswijk, C.A., Bakker, D., Hesseling, S.C., Koerten, H.K., Reactions of cells at implant surfaces (1991) Biomaterials, 12, pp. 187-193; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblasts to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface in vivo (1995) J Biomed Mat Res, 29, pp. 89-99; Pilliar, R.M., Porous-surface metallic implants for orthopedic applications (1987) J Biomed Mat Res, 21 (A1), pp. 1-33; Bobyn, J.D., Tanzer, M., Drygier, J.J., Du Joune, A.R., Brooks, C.E., Concerns with modularity in total hip arthroplasty (1994) Clin Orthop, 298, pp. 27-36; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dorr, L.D., Blocbaum, R., Emmanual, J., Meldrum, R., Histologic, biochemical and ion analysis of tissue and fluids retrieved during total hip arthroplasty (1990) Clin Orthop, 261, pp. 82-95; Hennig, F.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., Nickel-chromand cobalt-concentrations in human tissue and body fluids of hip prosthesis patients (1992) J Trace Elem Electrolytes Health Dis, 6, pp. 239-243; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 56 B, pp. 626-642; Deutman, R., Rulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J Bone Jt Surg, 59 A, pp. 862-865; Huo, M.H., Salvati, E.A., Lieberman, Jr., Betts, F., Bansal, M., Metallic debris in femoral endoseolysis in failed cemented total hip arthroplasties (1992) Clin Orthop, 276, pp. 157-168; Kirkpatrick, C.J., Mittermayer, C., Theoretical and practical aspects of testing potential biomaterials in vitro (1990) J Mat Mat Med, 1, pp. 9-13; Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regulatory Affairs, 4, pp. 13-22; Pizzoferrato, A., Ciapetti, G., Stea, S., Cell culture methods for testing biocompatibility (1994) Clin Mat, 15, pp. 173-190; Bizios, R., Mini review: Osteoblasts: An in vitro model of bone-implant interactions (1994) Biotechnol and Bioeng, 43, pp. 582-585; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 249-258; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures (1996) J Mater Sc Mater Med, 7, pp. 291-296; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., The use of rat, rabbit or human bone marrow derived cells for cytocompatibility evaluation of metallic elements (1997) J Mater Sc Mater Med, 8, pp. 233-238; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast-like cells: Part 1 - Retardation of tissue mineralisation by metal salts Biomaterials 1998; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J Mater Sci Mater Med, 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J Mater Sci Mater Med, 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , Doherty PJ et al., editors. Amsterdam: Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J Mater Sci Mater Med, 7, pp. 77-83; Pohler, O.E.M., Degradation of metallic orthopedic implants Biomaterials in Reconstructive Surgery, pp. 158-228. , Rubin LR, editor. St. Louis: C. V. Mosby, 1983; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tiss Res, 254, pp. 317-330; McGee-Russell, S.M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionized calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8, pp. 1174-1178; Fiske, C.H., Subbarow, Y., The colorimetric determination of phosphorus (1925) J Biol Chem, 66, pp. 373-400; Miller, J.C., Miller, J.N., (1993) Statistics for Analytical Chemistry (3rd Ed.), pp. 32-35. , Massen M, Tyson J, Stockwell P, Miller J, Chalmers R, Harwood E, editors. New York, London: Ellis Horwood, PTR Prentice Hall; De Bruijn, J.D., Cpat, K., De Groot, K., Van Blitterswijk, C.A., The ultrastructure of the one-hydroxyapatite interface in vitro (1992) J Biomed Mat Res, 26, pp. 1365-1382; Davies, J.E., Chernecky, R., Lowenberg, B., Shiga, A., Deposition and resorption of calcified matrix in vitro by rat marrow cells (1991) Cells and Mat, 1, pp. 3-15; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulte formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralization of osteoblastic cells derived from human bone (1990) Bone Min, 8, pp. 239-250; Cheng, S.L., Yang, J.W., Riffins, L., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29; Boskey, A.L., Stiner, D., Doty, S.B., Binderman, I., Levoy, P., Studies of mineralization in tissue culture: Optimal conditions for cartilage calcification (1992) Bone Min, 16, pp. 11-36; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Chung, C.H., Golub, E.E., Forbes, E., Mechanisms of action of β-glycerophosphate on bone cell mineralization (1992) Calcif Tissue Int, 51, pp. 305-311
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animal cell culture; Animals; article; ascorbic acid; atomic absorption spectrometry; Bioassay; Biomaterials; bone development; bone marrow cell; Bone Marrow Cells; Calcium; Calcium phosphates; Cell culture; Cell Death; Cells, Cultured; Corrosion; Corrosion products; culture medium; dexamethasone; electrochemical analysis; electrochemistry; Enzymes; glycerophosphate; histochemistry; Histocytochemistry; in vitro study; male; metal ion; Mineralisation; mineralization; nonhuman; ossification; osteoblast; Osteoblast-like cells; Osteoblasts; phosphate; Phosphate minerals; phosphorus; priority journal; rat; Rats; Rats, Wistar; Scanning electron microscopy; Slurries; Stainless steel; Stainless steel 316L; Stainless-steel corrosion products; Steel corrosion

ESR spectroscopy to determine the molecular mobility of poly(ethylene oxide) grafts in amphiphilic graft copolymers - Ji, J.; Feng, L.; Qiu, Y.; Yu, X. (Macromolecular Rapid CommunicationsMacromol. Rapid Commun., 1998)
The ethylene oxide (EO) mobility in polystyrene-graft-[poly(ethylene oxide)] (PS-g-PEO) and polystyrene-graft-[stearyl poly(ethylene oxide)] (PS-g-SPEO) copolymers was evaluated by spin probe techniques. The ESR spectra indicate that 4-hydroxyl-TEMPO (TEMPO = 2,2,6,6-tetramethylpiperidine-N-oxyl) is strongly biased to the PEO phase of the PS-g-(S)PEO membranes. The rotational correlation time τ c can also be employed to assess the PEO mobility in PS-g-(S)PEO membranes. Although τ c of PS-g-(S)PEO usually decreases with increasing surface density of EO, it is of interest that τ c is rather high when the surface within a depth of at least 5 nm is fully occupied by SPEO (sample PS-g-SPEO-72.6).
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: MRCOELanguage of Original Document: EnglishCorrespondence Address: Ji, J.; INEB-mat, Rua do Campo Alegre, 823, 4150 Porto, PortugalReferences: Bots, J.G.F., Van Der Does, L., Bentjes, A., (1986) Biomaterials, 7, p. 393;Osterberg, E., Holmberg, K., Schuman, T.P., Riggs, J.A., Burns, N.L., Van Alstine, J.M., Harris, J.M., (1995) J. Biomed. Mater. Res., 29, p. 741; Hubbell, J.A., (1997) Polym. Prepr. (Am. Chem. Soc., Div. Polym. Chem.), 38, p. 528; Harris, J.M., (1997) Polym. Prepr. (Am. Chem. Soc., Div. Polym. Chem.), 38, p. 520; Grainger, D.W., Okano, T., Kim, S.W., (1989) J. Colloid Interface Sci., 132, p. 161; Qiu, Y.X., Yu, X.J., Feng, L.X., Yang, S.L., (1992) Makromol. Chem., 193, p. 1377; Qiu, Y.X., Yu, X.J., Feng, L.X., Yang, S.L., (1992) Chin. J. Polym. Sci., 13, p. 112; Ranter, B.D., Graft Copolymer and Block Copolymer Surface (1985) Surface and Interfacial Aspects of Biomedical Polymers, 1, p. 374. , J. D. Andrade, Ed., Plenum Press, New York; Andrade, J.D., Gregonis, D.E., Smith, L.M., Polymer surface dynamic (1985) Surface and Interfacial Aspects of Biomedical Polymers, 1, p. 15. , J. D. Andrade, Ed., Plenum Press, New York; Liu, S.Q., Ito, Y., Imanish, Y., (1989) J. Biomater. Sci., Polym. Ed., 1, p. 111; Jeon, S.I., Lee, J.H., Andrade, J.D., De Gennes, P.G., (1991) J. Colloid Interface Sci., 142, p. 149; Takahara, A., Jo, N.J., Kajiyama, T., (1989) J. Biomater. Sci., Polym. Ed., 1, p. 17; Cameron, G.G., ESR Spectroscopy (1989) Comprehensive Polymer Science, Polymer Characterization, p. 517. , S. G. Allen, Ed; Hudson, A., Luckhurst, G.R., (1969) Chem. Rev., 69, p. 191; Neumann, A.W., Good, R.J., (1974) Surf. Colloid Sci., 4, p. 105; Caldararu, H., Caragheorgheopol, A., Donescu, D., Joela, H., (1994) J. Colloid Interface Sci., 173, p. 486

Evaluation of nickel toxicity on liver, spleen, and kidney of mice after administration of high-dose metal ion - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
The toxic effects caused by nickel (Ni) per si were explored by performing in vivo studies on mice following subcutaneous administration of a metallic solution of nickel at 1, 2, 3, and 4 weeks to evaluate the side effects of this metal ion when released from stainless steel implants. Other groups were similarly injected with HBSS and used as controls. Accumulation of Ni ions on liver, spleen, and kidney was assessed by an electrochemical method, adsorptive stripping voltammetry (AdSV) using microelectrodes, and atomic absorption spectrometry (AAS). Alterations of those organs induced by Ni ions were studied, showing that several histological changes had been induced. Chemical analysis and histological features indicate that Ni is partially accumulated in the study organs.The toxic effects caused by nickel (Ni) per si were explored by performing in vivo studies on mice following subcutaneous administration of a metallic solution of nickel at 1, 2, 3, and 4 weeks to evaluate the side effects of this metal ion when released from stainless steel implants. Other groups were similarly injected with HBSS and used as controls. Accumulation of Ni ions on liver, spleen, and kidney was assessed by an electrochemical method, adsorptive stripping voltammetry (AdSV) using microelectrodes, and atomic absorption spectrometry (AAS). Alterations of those organs induced by Ni ions were studied, showing that several histological changes had been induced. Chemical analysis and histological features indicate that Ni is partially accumulated in the study organs.
Cited By (since 1996): 27Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199804)40:1<40::AID-JBM5>3.0.CO;2-RPubMed ID: 9511097Language of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Instituto de Engenharia Biomedica, Faculdade de Engenharia, Universidade do Porto, Praca Coronel Pacheco, 1, 4050 Porto, PortugalChemicals/CAS: Nickel, 7440-02-0References: Cigada, A., Rondelli, G., Vicentini, B., Brunella, F., Dallaspezia, G., Corrosion behavior of high nitrogen stainless steels for biomedical applications (1994) Compatibility of Biomedical Implants, pp. 185-195. , P. Kovacs and N. S. Istephanous (eds.), The Electrochemical Society, Inc., Pennington, New Jersey;Bumgardner, J.D., Lucas, L.C., An evaluation of the corrosion properties and cellular compatibility of nickel-based dental casting alloys (1994) Compatibility of Biomedical Implants, pp. 241-252. , P. Kovacs and N. S. Istephanous (eds.), The Electrochemical Society, Inc., Pennington, New Jersey; Williams, D.F., (1990) Encyclopedia of Medical and Dental Materials, , Pergamon Press, Oxford; Muller, A.W.J., Maessen, F.J.M.J., Davidson, C.L., Determination of the corrosion rates of six dental NiCrMo alloys in an artificial saliva by chemical analysis of the medium using ICP-AES (1990) Dent. Mater., 6, pp. 63-68; Bumgardner, J.D., Lucas, L.C., Surface analysis of nickel-chromium dental alloys (1993) Dent. Mater., 9, pp. 252-259; Williams, D.F., (1981) Systemic Aspects of Biocompatibility, 1-2. , CRC Press, Boca Raton, Florida; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel products cause alterations on mouse spleen cellular populations (1995) J. Mater. Sci. Mater. Med., 6, pp. 56-61; Tracana, R.B., Sousa, J.P., Carvalho, G.S., Mouse inflammatory response to stainless steel corrosion products (1994) J. Mater. Sci. Mater. Med., 5, pp. 596-600; Jacks, J.J., Skiper, A.K., Black, J., Urban, R.M., Galante, J.O., Release and excretion of metal in patients who have a total hip replacement component made of titanium base alloy (1991) J. Bone Joint Surg., 73 A, pp. 1475-1486; Stulberg, B.N., Merrit, K., Bawer, T.W., Metallic wear debris in metal backed patellar failure (1994) J. Appl. Biomater., 5, pp. 9-16; Panigutti, M.A., Merrit, K., Bruner, R.J., Kraay, M.J., Brown, S.A., Correlation of allergy, metal levels, implant alloy, and implant damage in patients undergoing revision joint arthroplastics (1992) Trans. Soc. Biomater., 15, p. 7; Abreu, A.M., Tracana, R.B., Carvalho, G.S., Sousa, J.P., Determination of metal ions released from metallic biomaterials using absorption spectroscopy and microelectrodes (1995) Biomed. Lett., 52, pp. 133-148; (1986) Health Assessment Document for Nickel and Nickel Compounds, , EPA/600/8-83/012FF, U.S. Environmental Protection Agency, Research Triangle Park, North Carolina; Black, J., (1988) Orthopedic Biomaterials in Research and Practice, , Churchill Livingstone, New York; Nieboer, E., Rossetto, F.E., Menon, C.R., Toxicology of nickel compounds (1980) Nickel Toxicology, pp. 359-401. , S. S. Brown and F. W. Sunderman, Jr. (eds.), Academic Press, Inc., New York; Pereira, M.L., Pereira, M.C., Sousa, J.P., Evaluation of nickel effects on mouse liver: Tissue response and metal ion accumulation (1995) Biomed. Lett., 52, pp. 235-244; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive stripping voltammetry using mercury microelectrodes (1996) Electroanalysis, 9, pp. 1-5; Black, J., Systemic distribution and excretion (1981) Biomedical Engineering and Instrumentation, p. 180. , R. Plonsey and J. L. Katz (eds.), Marcel Dekker, Inc., New York; Pohler, O.E.M., Degradation of metallic orthopedic implants (1983) Biomaterials in Reconstructive Surgery, p. 197. , L. R. Rugin (ed.), The C. V. Mosby Company, St. Louis; Ross, M.H., Romrell, L.J., (1989) Histology - A Text and Atlas, , Williams and Wilkins, New York
Keywords: Absorption spectroscopy; Adsorptive stripping voltammetry; animal experiment; animal tissue; Animals; article; atomic absorption spectrometry; biomaterial; body weight; controlled study; Dose-Response Relationship, Drug; electrochemistry; Evaluation Studies; histology; Implants (surgical); Kidney; Liver; liver toxicity; Living systems studies; Mice; Microelectrodes; mouse; nephrotoxicity; Nickel; nonhuman; potentiometry; Spectrophotometry, Atomic; Spleen; spleen injury; Stainless steel; toxicity

Flow cytometry for assessing biocompatibility - Lopes, M.A.; Knowles, J.C.; Kuru, L.; Santos, J.D.; Monteiro, F.J.; Olsen, I. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 1998)
Flow cytometry (FCM) was examined as a possible procedure for measuring in vitro the biocompatibility of implant materials for orthopedic and dental surgery. The human osteoblast-like cell line MG63 was grown on hydroxyapatite (HA) and P 2O 5 glass-reinforced HA composite discs and compared with the same cells grown on polystyrene culture dishes. While morphological observation at the light and electron microscopic levels showed no major deleterious effects, FCM indicated that cell size was somewhat reduced, particularly by growth on the HA composite. Moreover, this material also appeared to delay the progression of the cells from the G0/G1 into the S phase of the cell cycle. In addition to this low level of inhibition of cell growth relative to control cultures, FCM analysis also demonstrated that the glass-reinforced HA caused some down-regulation of the expression of osteocalcin and fibronectin, two antigens which play a vital part in the integrity and function of bone and soft connective tissue, respectively. These results thus show, first, that although HA and the HA composite used in these experiments were generally biocompatible, they nevertheless had certain suboptimal effects on the cells; and second, that FCM could be a highly useful procedure for effectively screening and evaluating important biological responses to implant materials. Flow cytometry (FCM) was examined as a possible procedure for measuring in vitro the biocompatibility of implant materials for orthopedic and dental surgery. The human osteoblast-like cell line MG63 was grown on hydroxyapatite (HA) and P 2O 5 glass-reinforced HA composite discs and compared with the same cells grown on polystyrene culture dishes. While morphological observation at the light and electron microscopic levels showed no major deleterious effects, FCM indicated that cell size was somewhat reduced, particularly by growth on the HA composite. Moreover, this material also appeared to delay the progression of the cells from the G0/G1 into the S phase of the cell cycle. In addition to this low level of inhibition of cell growth relative to control cultures, FCM analysis also demonstrated that the glass-reinforced HA caused some down-regulation of the expression of osteocalcin and fibronectin, two antigens which play a vital part in the integrity and function of bone and soft connective tissue, respectively. These results thus show, first, that although HA and the HA composite used in these experiments were generally biocompatible, they nevertheless had certain suboptimal effects on the cells; and second, that FCM could be a highly useful procedure for effectively screening and evaluating important biological responses to implant materials.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(19980915)41:4<649::AID-JBM17>3.0.CO;2-9PubMed ID: 9697038Language of Original Document: EnglishCorrespondence Address: Olsen, I.; Department of Periodontology, Eastman Dental Institute, University of London, 256 Gray's Inn Rd., London WC1X 8LD, United KingdomChemicals/CAS: Biocompatible Materials; Collagen, 9007-34-5; Dental Implants; Fibronectins; Osteocalcin, 104982-03-8References: Kirkpatrick, C.J., A critical view of current and proposed methodologies for biocompatibility testing: Cytotoxicity in vitro (1992) Regul. Affairs, 4, pp. 13-32;Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Ariola, C.R., Granchi, D., Savarino, L., Cell culture methods for testing biocompatibility (1994) Clin. Mater., 15, pp. 173-190; Puleo, D.A., Preston, K.E., Shaffer, J.B., Bizios, R., Examination of osteoblast-orthopaedic biomaterial interactions using molecular techniques (1993) Biomaterials, 14, pp. 111-114; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J. Mater. Sci. Mater. Med., 7, pp. 637-643; Macey, M.G., (1994) Flow Cytometry: Clinical Applications, , Blackwell Scientific Publications, Oxford; Salzman, G.C., Singham, S.B., Johnston, R.G., Bohren, C.F., Light scattering and cytometry (1990) Flow Cytometry and Sorting, pp. 81-107. , M. R. Melamed, T. Lindmo, and M. L. Mendelsohn (eds.), Wiley-Liss, New York; Corver, W.E., Cornelisse, C.J., Fleuren, G.J., Simultaneous measurement of two cellular antigens and DNA using fluorescein-isothiocyanate, R-phycoerythrin and propidium iodide on a standard FACScan (1994) Cytometry, 15, pp. 117-128; Macon, W.R., Salhany, K.E., TI- T-cell subset analysis of paraffin-embedded peripheral T-cell lymphomas (PTCLs) with correlation of CD4/CD8 results by flow cytometry (FACs) (1997) Lab. Invest., 76, p. 753; Kuru, L., Parkar, M.H., Griffiths, G.S., Newman, H.N., Olsen, I., Flow cytometry analysis of functionally distinct gingival and periodontal ligament cells (1998) J. Dent. Res., 77, pp. 555-564; Kamiya, I., Okuda, K., Hara, K., Flow cytometric identification and detection of Porphromonas gingivalis by an LPS specific monoclonal antibody (1994) J. Periodontol., 65, pp. 309-315; Sumner, H., Abraham, D., Bou-Gharios, G., Plater-Zyberk, C., Olsen, I., Simultaneous measurement of cell surface and intracellular antigens by multiple flow cytometry (1991) J. Immunol. Methods, 136, pp. 259-267; Beauchamp, J.R., Abraham, D.J., Bou-Gharios, G., Partridge, T.A., Olsen, I., Expression and function of adhesion molecules during differentiation of human skeletal muscle in culture (1992) Am. J. Pathol., 140, pp. 387-401; Abraham, D., Lupoli, S., McWhirter, A., Plater-Zyberk, C., Piela, T.H., Korn, J., Olsen, I., Black, C., Expression and function of surface antigens on scleroderma fibroblasts (1991) Arthritis Rheum., 34, pp. 1164-1172; Bou-Gharios, G., Osman, J., Black, C., Olsen, I., Excess matrix accumulation in scleroderma is caused partly by differential regulation of stromelysin and TIMP-1 synthesis (1994) Clin. Chim. Acta, 231, pp. 69-78; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Best, S., Sim, B., Kayser, M., Downes, S., The dependence of osteoblastic response on variations in the chemical composition and physical properties of hydroxyapatite (1997) J. Mater. Sci. Mater. Med., 8, pp. 97-103; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., Effect of titanium surface roughness on proliferation, differentiation and protein synthesis of human osteoblast-like cells (MG-63) (1995) J. Biomed. Mater. Res., 29, pp. 389-401; Granchi, D., Stea, S., Ciapetti, G., Savarino, L., Cavedagna, D., Pizzoferatto, A., In vitro effects of bone cements on the cell cycle of osteoblast-like cells (1995) Biomaterials, 16, pp. 1187-1192; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Scharla, S.H., Strong, D.D., Rosen, C., Mohan, S., Holick, M., Baylink, D.J., Linkhart, T.A., 1,25-Dihydroxyvitamin D3 increases secretion of insulin-like growth factor binding protein-4 (IGFBP-4) by human osteoblast-like cells in vitro and elevates IGFBP-4 serum levels in vivo (1993) J. Clin. Endocrinol. Metabol., 77, pp. 1190-1197; De Bart, A.C., Quax, P.H., Lowik, C.W., Verheijen, J.H., Regulation of plasminogen activation, matrix metalloproteinases and urokinase-type plasminogen activator-mediated extracellular matrix degradation in human osteosarcoma cell line MG63 by interleukin-1 alpha (1995) J. Bone Min. Res., 19, pp. 1374-1384; Barille, S., Collette, M., Bataille, R., Amiot, M., Myeloma cells upregulate interleukin-6 secretion in osteoblastic cells through cell-to-cell contact but downregulate osteocalcin (1995) Blood, 86, pp. 3151-3159; Maillard, C., Malaval, L., Delmas, P.D., Immunological screening of SPARC/osteonectin in nonmineralized tissue (1992) Bone, 13, pp. 257-264; Bou-Gharios, G., Osman, J., Atherton, A., Monoghan, P., Vancheeswaran, R., Black, C., Olsen, I., Expression of ectopeptidases in scleroderma (1995) Ann. Rheum. Dis., 54, pp. 111-116; Goseki, T., Shimizu, N., Iwasawa, T., Takiguchi, H., Abiko, Y., Effects of in vitro cellular aging on alkaline phosphatase, cathepsin activities and collagen secretion of human peridontal ligament-derived cells (1996) Mech. Age. Dev., 91, pp. 1761-11183; Hallab, N.J., Bundy, K.J., O'Connor, K., Clark, R., Moses, R.L., Cell adhesion to biomaterials: Correlations between surface charge, surface roughness, adsorbed protein and cell morphology (1995) J. Long-Term Effects Med. Implants, 5, pp. 209-231; Kieswetter, K., Schwartz, Z., Hummert, T.W., Cochran, D.L., Simpson, J., Sean, D.P., Boyan, B.D., Surface roughness modulates the local production of growth factors and cytokines by osteoblast-like MG-63 cells (1996) J. Biomed. Mater. Res., 32, pp. 55-63; Altankov, G., Grinnell, F., Groth, T., Studies on the biocompatibility of materials: Fibroblast reorganization of substratumbound fibronectin on surfaces varying in wettability (1996) J, Biomed. Mater. Res., 30, pp. 385-391; Chesmel, K.D., Clark, C.C., Brighton, C.T., Black, J., Cellular response to chemical and morphologic aspects of biomaterial surfaces. II. The biosynthetic and migratory response of bone cell populations (1995) J. Biomed. Mater. Res., 29, pp. 1101-1110; Nishizawa, K., Toriyama, M., Suzuki, T., Kawamoto, Y., Yokogawa, Y., Nagae, H., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal cells (1993) J. Ferment. Bioeng., 75, pp. 435-437; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J. Biomed. Mater. Res., 39, pp. 244-251
Keywords: antigen expression; Antigens; Biocompatibility; Biocompatible Materials; biomaterial; Biomaterials; Biomedical engineering; Bone and Bones; bone prosthesis; Cell culture; cell cycle; cell cycle s phase; Cell Line; Cell size; cell ultrastructure; Cells; Collagen; conference paper; Dental Implants; dentistry; extracellular matrix; Fibronectin; Fibronectins; flow cytometry; Glass fiber reinforced plastics; growth inhibition; human; human cell; Humans; hydroxyapatite; Implants; Implants (surgical); Microscopy, Electron, Scanning; mitosis inhibition; morphology; orthopedics; Osteoblasts; osteocalcin; Polystyrenes; Prostheses and Implants; prosthesis material; Tissue; tooth prosthesis

In situ characterization of the p-Si/NH 4F interface during dissolution in the current oscillations regime - Cattarin, S.; Chazalviel, J.-N.; Da Fonseca, C.; Ozanam, F.; Peter, L.M.; Schlichthörl, G.; Stumper, J. (Journal of the Electrochemical SocietyJ Electrochem Soc, 1998)
Several physicochemical properties of the p-Si/NH 4F interface have been monitored by in situ techniques in the regime of current oscillations. Comparison of evolution of infrared absorption, microwave reflectivity, electrode admittance, hydrogen evolution, and electron injection rate shows interesting correlations. An integrated description of the processes involved is attempted on the basis of the current models for the Si/acidic fluoride interface.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: JESOALanguage of Original Document: EnglishCorrespondence Address: Cattarin, S.; Ist. Polarografia ed E., C. N. R., 35100 Padova, ItalyReferences: Zhang, X.G., Collins, S.D., Smith, R.L., (1989) This Journal, 136, p. 1561;Smith, R.L., Collins, S.D., (1992) J. Appl. Phys., 71, pp. R1; Jung, K.H., Shih, S., Kwong, D.L., (1993) This Journal, 140, p. 3046; Lewerenz, H.J., Stumper, J., Pettenkofer, C., Greef, R., (1989) Electrochim. Acta, 34, p. 1729; Bitzer, T., Lewerenz, H.J., (1992) Surf. Sci., 269-270, p. 886; Lewerenz, H.J., Bitzer, T., Gruyters, M., Jacobi, K., (1993) This Journal, 140, pp. L44; Lewerenz, H.J., (1992) Electrochim. Acta, 37, p. 847; Chazalviel, J.-N., (1992) Electrochim. Acta, 37, p. 865; Ozanam, F., Chazalviel, J.-N., (1993) J. Electron Spec. Rel. Phenomena, 64-65, p. 395; Ozanam, F., Da Fonseca, C., Chazalviel, J.-N., (1995) Proc. Indian Acad. Sci. (Chem. Sci.), 107, p. 709; Da Fonseca, C., Ozanam, F., Chazalviel, J.-N., (1996) Surface Science, 365, p. 1; Stumper, J., Peter, L.M., (1991) J. Electroanal. Chem., 309, p. 325; Stumper, J., Greef, R., Peter, L.M., (1991) J. Electroanal. Chem., 310, p. 445; Blackwood, D.J., Borazio, A., Greef, R., Peter, L.M., Stumper, J., (1992) Electrochim. Acta, 37, p. 889; Gerischer, H., Lüke, M., (1988) Ber. Bunsenges. Phys. Chem., 92, p. 573; Chazalviel, J.-N., Ozanam, F., Etman, M., Paolucci, F., Peter, L.M., Stumper, J., (1992) J. Electroanal. Chem., 327, p. 343; Aggour, M., Giersig, M., Lewerenz, H.-J., (1995) J. Electroanal. Chem., 383, p. 67; Lehmann, V., (1996) This Journal, 143, p. 1313; Lewerenz, H.J., Aggour, M., (1993) J. Electroanal. Chem., 351, p. 159; Chazalviel, J.-N., Ozanam, F., (1992) This Journal, 139, p. 2501; Cattarin, S., Peter, L.M., Jason Riley, D., (1997) J. Phys. Chem. B, 101, p. 4071; Kirk, C.T., (1988) Phys. Rev. B, 38, p. 1255; Schlichtörl, G., Peter, L.M., (1994) This Journal, 141, pp. L171; Myamlin, V.A., Pleskov, Y.V., (1967) Electrochemistry of Semiconductors, p. 213. , Plenum Press, New York; Chazalviel, J.-N., Da Fonseca, C., Ozanam, F., To be publishedPankove, J.I., (1971) Optical Processes in Semiconductors, p. 75. , Prentice-Hall Inc., Englewood Cliffs, NJ; Tardella, A., Chazalviel, J.-N., (1985) Phys. Rev. B, 32, p. 2439; Peter, L.M., Schlichthörl, G., In preparationRappich, J., Timoshenko, V.Y., Dittrich, T., (1997) Ber. Bunsenges. Phys. Chem., 101, p. 139; Matsumura, M., Morrison, S.R., (1983) J. Electroanal. Chem., 147, p. 157; Franck, U.F., (1974) Faraday Symp. Chem. Soc., 9, p. 137
Keywords: Ammonium compounds; Ammonium fluoride; Dissolution; Electric currents; Electric Impedance; Electrochemical electrodes; Electron injection rate; Hydrogen; Interfaces (materials); Microwave reflectivity; Porous silicon

In situ infrared study of the oscillating anodic dissolution of silicon in fluoride electrolytes - Chazalviel, J.-N.; Da Fonseca, C.; Ozanam, F. (Journal of the Electrochemical SocietyJ Electrochem Soc, 1998)
In the far anodic regime, the anodic dissolution of silicon exhibits a resonant behavior, which results from an oscillating behavior on the microscopic scale. The interface has been investigated using in situ infrared spectroscopy in the strong oscillating regime. The interface oxide film varies in thickness by up to a factor of two, and the oxide quality, as determined from a fine analysis of the infrared polarized spectra, is also found to vary periodically during the oscillation. The relative phase of these periodic variations suggests that the origin of the oscillation mechanism lies in a periodic breakdown of the blocking properties of the oxide, which may be initiated by ion permeation in the outer part of the film. The study of oxide dissolution kinetics evidences a stratified structure of the oxide, with layers of "soft" and "strong" oxide. The fast dissolution of the soft oxide is associated with the periodic drop of the oxide thickness.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JESOALanguage of Original Document: EnglishCorrespondence Address: Chazalviel, J.-N.; Lab. de Phys. de la Matiere Cond., U. de Rech. Associée, CNRS-École Polytechnique, F-91128 Palaiseau-Cedex, FranceReferences: Gerischer, H., Lübke, M., (1988) Ber. Bunsenges. Phys. Chem., 92, p. 573;Gershinskii, A.E., Mironova, L.V., (1989) Élektrokhimiya, 25, p. 1374; (1990) Sov. Electrochem., 25, p. 1224; Chazalviel, J.-N., Etman, M., Ozanam, F., (1991) J. Electroanal. Chem., 297, p. 533; Hassan, H.H., Sculfort, J.-L., Etman, M., Ozanam, F., Chazalviel, J.-N., (1995) J. Electroanal. Chem., 380, p. 55; Hassan, H.H., Fotouhi, B., Sculfort, J.-L., Abdel-Rehiem, S.S., Etman, M., Ozanam, F., Chazalviel, J.-N., (1996) J. Electroanal. Chem., 407, p. 105; Chazalviel, J.-N., (1992) Electrochim. Acta, 37, p. 865; Da Fonseca, C., Ozanam, F., Chazalviel, J.-N., (1996) Surf. Sci., 365, p. 1; Turner, D.R., (1958) This Journal, 105, p. 402; Ozanam, F., Chazalviel, J.-N., Radi, A., Etman, M., (1991) Ber. Bunsenges. Phys. Chem., 95, p. 98; Ozanam, F., Chazalviel, J.-N., Radi, A., Etman, M., (1992) J. Electrochem. Soc., 139, p. 2491; Stumper, J., Greef, R., Peter, L.M., (1991) J. Electroanal. Chem., 310, p. 445; Lewerenz, H.J., Schlichthörl, G., (1992) J. Electroanal. Chem., 327, p. 85; Chazalviel, J.-N., Ozanam, F., Etman, M., Paolucci, F., Peter, L.M., Stumper, J., (1992) J. Electroanal. Chem., 327, p. 343; Chazalviel, J.-N., Ozanam, F., (1992) J. Electrochem. Soc., 139, p. 2501; Lewerenz, H.J., Aggour, M., (1993) J. Electroanal. Chem., 351, p. 159; Lehmann, V., (1995) J. Electrochem. Soc., 143, p. 1313; Ozanam, F., Chazalviel, J.-N., (1993) J. Electron Spectrosc. Relat. Phenom., 64-65, p. 395; Ozanam, F., Da Fonseca, C., Chazalviel, J.-N., (1995) Proc. Indian Acad. Sci. Chem. Sci., 107, p. 709; Da Fonseca, C., Ozanam, F., Chazalviel, J.-N., (1997) Mikrochim. Acta (Suppl.), 14, p. 811; Cattarin, S., Chazalviel, J.-N., Da Fonseca, C., Ozanam, F., Peter, L.M., Schlichthörl, G., Stumper, J., (1998) J. Electrochem. Soc., 145, p. 498; Matsumura, M., Morrison, S.R., (1983) J. Electroanal. Chem., 147, p. 157; Lewerenz, H.J., (1992) Electrochim. Acta, 37, p. 847; Harbecke, B., Heinz, B., Grosse, P., (1985) Appl. Phys. A, 38, p. 263; Gaskell, P.H., Johnson, D.W., (1976) J. Non-Cryst. Solids, 20, p. 171; Kirk, C.T., (1988) Phys. Rev. B, 38, p. 1255; Ozanam, F., Da Fonseca, C., Venkateswara Rao, A., Chazalviel, J.-N., (1997) Appl. Spectrosc., 51, p. 519; Crozier, D., Douglas, R.W., (1965) Phys. Chem. Glasses, 6, p. 240; Handke, M., Mozgawa, W., (1993) Vib. Spectrosc., 5, p. 75; Aggour, M., Giersig, M., Lewerenz, H.J., (1995) J. Electroanal. Chem., 383, p. 67; Sharpe, C.D., Lilley, P., (1980) J. Electrochem. Soc., 127, p. 1918; Peiner, E., Schlachetzki, A., (1992) J. Electrochem. Soc., 139, p. 552; Chazalviel, J.-N., Unpublished workBerreman, D.W., (1963) Phys. Rev., 130, p. 2193
Keywords: Anodic dissolution; Anodic oxidation; Dissolution; infrared spectroscopy; Interfaces (materials); Oxide films; Oxides; Semiconducting silicon

In vitro biomineralization by osteoblast-like cells I. Retardation of tissue mineralization by metal salts - Morais, S.; Sousa, J.P.; Fernandes, M.H.; Carvalho, G.S. (BiomaterialsBiomaterials, 1998)
The cytocompatibility of stainless steel 316L (SS 316L) corrosion products was investigated with particular focus on the dose- and time-effect of electrochemically dissolved SS and the corresponding separate metal ions on osteogenic bone marrow derived cells. Type AISI 316L stainless steel (Fe 63.9%, Cr 18.0%, Ni 12.5%, Mo 2.8%, Si 1.2%, Mn 1.6% and C 0.025%, weight for weight) was anodically dissolved in Hank's Balanced Salt Solution (HBSS) and diluted to the following concentrations: 500 μgml
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00149-XPubMed ID: 9678845Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; IEC, Universidade do Minho, Largo do Paco, 4719 Braga Codex, PortugalChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Cations; Chromium, 7440-47-3; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphates; Stainless Steel, 12597-68-1; Tetrazolium Salts; Thiazoles; thiazolyl blue, 298-93-1References: Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 56 B, pp. 626-642;Deutman, R., Rulder, T.J., Brian, R., Nater, J.P., Metal sensitivity before and after total hip arthroplasty (1977) J Bone Jt Surg, 59 A, pp. 862-865; Bartolozzi, A., Black, J., Chromium concentrations in serum, blood clot and urine from patients following total hip arthroplasty (1985) Biomaterials, 6, pp. 2-8; Dorr, L.D., Blocbaum, R., Emmanual, J., Meldrum, R., Histologic, biochemical and ion analysis of tissue and fluids retrieved during total hip arthroplasty (1990) Clin Orthop, 261, pp. 82-95; Henning, F.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., Nickel-, chromium- and cobalt-concentrations in human tissue and body fluids of hip prosthesis patients (1992) J Trace Elem Electrolytes Health Dis, 6, pp. 239-243; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures (1996) J Mater Sci Mater Med, 7, pp. 291-296; Tomás, H., Carvalho, G.S., Fernandes, M.H., Freire, A.P., Abrantes, L.M., The use of rat, rabbit or human bone marrow derived cells for cytocompatibility evaluation of metallic elements (1997) J Mater Sci Mater Med, 8, pp. 233-238; Pules, D.A., Huh, W.W., Acute toxicity of metal ions in cultures of osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 109-116; Thompson, G.J., Pules, D.A., Effects of sublethal metal ion concentrations on osteogenic cells derived from bone marrow stromal cells (1995) J Appl Biomater, 6, pp. 249-258; McGee-Russell, S.M., Histochemical methods for calcium (1958) J Histochem Cytochem, 6, pp. 22-42; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Wong, M., Rao, L.G., Li, H., Long-term effects of physiologic concentrations of dexamethasone on human bone derived cells (1990) J Bone Miner Res, 5, pp. 803-813; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblast phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 143, pp. 213-221; Gotoh, Y., Hiraiwa, K., Narajama, M., In vitro mineralisation of osteoblastic cells derived from human bone (1990) Bone Miner, 8, pp. 239-250; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralisation of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Miner, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralisation of osteoid nodules in vitro (1992) Bone Miner, 17, pp. 15-29; Chung, C.H., Golub, E.E., Forbes, E., Mechanisms of action of β-glycerophosphate on bone cell mineralisation (1992) Calcif Tissue Int, 51, pp. 305-311; Schimdt, R., Kulbe, K.D., Long term cultivation of human osteoblasts (1993) Bone Miner, 20, pp. 211-221; Cheng, S.L., Yang, J.W., Riffins, L., Differentiation of human bone marrow osteogenic stromal cells in vitro. Induction of the osteoblast phenotype by dexamethasone (1994) Endocrinology, 134, pp. 277-286; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralisation in serially passaged human alveolar bone cells (1997) J Mater Sci Mater Med, 8, pp. 73-76; Martin, A., Clynes, M., Comparison of 5 microplate colorimetric assays for in vitro cytotoxicity testing and cell proliferation assays (1993) Cytotechnology, 11, pp. 49-58; Sgouras, D., Duncan, R., Methods for the evaluation of biocompatibility of soluble synthetic polymers which have potential for biomedical use. 1. Use of the tetrazolium-based colorimetric assay (MTT) as a preliminary screen for evaluation of in vitro cytotoxicity (1990) J Mater Sci Mater Med, 1, pp. 61-68; Ciapetti, G., Cenni, E., Stea, S., Pizzoferrato, A., In vitro evaluation of cell/biomatrial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Yoshimura, T., Kurita, C., Hayata, M., Nagai, H., Diagnosis of drug allergy by the lymphocyte stimulation test with the MTT (3-(4,5-dimethyl thiazol-2-yl)-2,2-diphenyl tetrazolium bromide) assay (1993) Biol Pharm Bull, 16, pp. 686-689; Sasanaluckit, P., Albustany, K.R., Doherty, P.J., Williams, D.F., Biocompatibility of glass ionomer cements (1993) Biomaterials, 14, pp. 906-916; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1996) J Mater Sci Mater Med, 7, pp. 77-83; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., Histological and biochemical evaluation of osteoblasts cultured on bioactive glass, hydroxylapatite, titanium alloy and stainless steel (1993) J Biomed Mater Res, 27, pp. 465-475; Owen, M., Marrow stromal stem cells (1988) J Cell Sci, 10, pp. 63-76; Beresford, J.N., Osteogenic stem cells and the stromal system of bone and marrow (1989) Clin Orthop Rel Res, 240, pp. 270-280; Owen, T.A., Arohow, M., Shalhonb, V., Progressive development of the rat osteoblast phenotype in vitro: Reciprocal relationships in expression of genes associated with osteoblast proliferation during formation of bone extracellular matrix (1990) J Cell Phys, 143, pp. 420-430; Malaval, L., Modrowski, D., Gupta, K., Aubin, J.E., Cellular expression of bone related proteins during in vitro osteogenesis in rat bone marrow stromal cell cultures (1994) J Cell Phys, 158, pp. 555-572; Stein, G.S., Lion, J.B., Molecular mechanisms mediated proliferation-differentiation interrelationships during progressive development of the osteoblast phenotype: Update 1995 (1995) End Rev, 4, pp. 290-297
Keywords: Absorption spectroscopy; alkaline phosphatase; animal cell; Animalia; Animals; article; ascorbic acid; atomic absorption spectrometry; balanced salt solution; Bioassay; Biocompatibility; biomaterial; Biomaterials; biomineralization; bone marrow cell; bone mineralization; Bovinae; Calcification, Physiologic; Calcium; calcium phosphate; Carbon; Cations; Cattle; Cell Division; cell proliferation; cell survival; cell viability; Cells, Cultured; Chromium; controlled study; Corrosion; dexamethasone; electrochemistry; enzyme activity; Enzyme kinetics; glycerol 2 phosphate; histochemistry; Iron; Kinetics; manganese; metal ion; Metal ions; Metals; molybdenum; Nickel; nonhuman; Oryctolagus cuniculus; osteoblast; Osteoblast cells; Osteoblast-like cells; Osteoblasts; Phosphates; priority journal; rabbit; Rabbits; serum; Silicon; Stainless steel; Steel corrosion; Tetrazolium Salts; Thiazoles; Tissue culture

In vitro biomineralization by osteoblast-like cells II. Characterization of cellular culture supernatants - Morais, S.; Carvalho, G.S.; Faria, J.L.; Gomes, H.T.; Sousa, J.P. (BiomaterialsBiomaterials, 1998)
The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analysing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy. X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was oberved that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.The quantification of total calcium, phosphorus, iron, chromium and nickel in cell culture medium by electrochemical or spectroscopic means may require digestion of samples. Nevertheless, when pH adjustment is performed for values higher than about 6.5, the formation of two phases occurs: a white precipitate and a clear solution. Analyzing both phases using microelectrodes, atomic absorption spectrometry (AAS), diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy, X-ray dispersive (XRD) analysis, scanning electron microscopy (SEM) and energy dispersive spectroscopic (EDS) analysis, it was observed that iron, chromium and nickel are not co-precipitating with the white solid phase. If quantification of calcium, phosphorus and magnesium is intended, a ten-fold dilution at least, must be performed to avoid most of these elements going into the precipitate. This knowledge is crucial if a mineralization study is going to be made.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00150-6PubMed ID: 9678846Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; IEC, Universidade do Minho, Largo do Paco, 4719 Braga Codex, PortugalChemicals/CAS: Calcium, 7440-70-2; Chromium, 7440-47-3; Culture Media; Iron, 7439-89-6; Metals; Nickel, 7440-02-0; Phosphorus, 7723-14-0; Stainless Steel, 12597-68-1References: Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., Toxic effects caused by stainless steel corrosion products on mouse seminiferous cells (1994) Cytobios, 77, pp. 73-80;Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Chromium accumulation and ultrastructural changes in the mouse liver caused by stainless steel corrosion products (1995) J Mater Sci Mater Med, 6, pp. 523-527; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., Stainless steel corrosion products cause alterations on mouse spleen cellular populations (1995) J Mater Sci Mater Med, 6, pp. 56-61; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., Metals electrochemically dissolved in human serum inhibit T-lymphocyte function (1992) Advances in Biomaterials, pp. 7-11. , Doherty PJ, et al., editors. Amsterdam: Elsevier; Carvalho, G.S., Castanheira, M., Diogo, I., Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts (1995) J Mater Sci Mater Med, 7, pp. 77-83; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro bone formation in the presence of stainless steel corrosion products (1994) Poster Section, 11th European Conference on Biomaterials, , Pisa, Italy; Sousa, J.P., Requirements in materials for biosensors J Mater Sci Mater Med, , in press; Morais, S., Sousa, J.P., Fernandes, M.H., Carvalho, G.S., In vitro biomineralisation by osteoblast like cells. I. Retardation of tissue mineralisation by metal salts (1998) Biomaterials, 19, pp. 13-21; Morais, S., Carvalho, G.S., Sousa, J.P., Determination of nickel in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with mercury microelectrodes (1997) Electroanalysis, 9 (5), pp. 422-426; Morais, S., Carvalho, G.S., Sousa, J.P., Optimization study for nickel quantification in cell culture medium using mercury film microelectrodes (1996) Portugaliae Electrochimica Acta, 14, pp. 267-272; Morais, S., Carvalho, G.S., Sousa, J.P., Iron determination in osteoblast-like cell culture medium by adsorptive cathodic stripping voltammetry with a mercury microelectrode (1997) Electroanalysis, 9, pp. 791-795; Morais, S., Carvalho, G.S., Sousa, J.P., Chromium determination in osteoblast-like cell culture medium by catalytic stripping voltammetry with a mercury microelectrode Electroanalysis, , submitted for publication; Morais, S., Carvalho, G.S., Sousa, J.P., Potentiometric determination of total and ionised calcium in osteoblast-like cell culture medium (1996) Electroanalysis, 8 (12), pp. 1174-1178; Morais, S., Carvalho, G.S., Sousa, J.P., Inorganic phosphorus determination in osteoblast-like cell culture for in vitro mineralisation study (1996) Poster Section, 15th Meeting of the Portuguese Chemical Society, , Porto; Pend, J., Jin, W., Anodic stripping voltammetric determination of trace lead in micro-samples with a mercury ultramicroelectrode (1992) Anal Chim Acta, 264, pp. 213-219; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., Nickel quantification in mice organs by adsorptive cathodic stripping voltammetry using mercury microelectrodes (1997) Electroanalysis, 9, p. 1501; Wurfels, W., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid. Part 3a (1989) Anal Chim Acta, 226, pp. 31-41; Wurfels, W., Jackwerth, E., Stoeppler, M., Residues from biological materials after pressure decomposition with nitric acid. Part 2a (1989) Anal Chim Acta, 226, pp. 17-30; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, R., Tolg, G., Wet mineralisation of organic matrices in glassy carbon vessels in a pressure-bomb system for trace element analysis (1979) Talanta, 26, pp. 681-691; Nakamoto, K., (1970) Infrared Spectra of Inorganic and Coordination Compounds, 2nd Edn., , NY: Wiley Interscience; Lin-Vien, D., Colthup, N.B., Fateley, W.G., Grasselli, J.G., (1991) The Handbook of Infrared and Raman Characteristic Frequencies of Organic Molecules, , Boston: Academic Press; Walsh, W.R., Christiansen, D.L., Demineralized bone matrix as a template for mineral-organic composites (1995) Biomaterials, 16 (18), pp. 1363-1371; Koeneman, J., Lemons, J., Ducheyne, P., Lacefield, W., Magee, F., Calahan, K.J., Workshop on characterisation of calcium phosphate materials (1990) J Appl Biomater, 1, pp. 79-90; Mann, S., Webb, J., Williams, R.J.P., (1989) Biomineralization: Chemical and Biochemical Perspectives, , Germany: VCH, Weinheim; Evans, E.M., Freeman, M.A.R., Miller, A.J., Vernon-Roberts, B., Metal sensitivity as a cause of bone necrosis and loosening of the prosthesis in total joint replacement (1974) J Bone Jt Surg, 566, pp. 626-642; De Vernejoul, M.C., Pointillart, A., Golenzer, C.C., Metals in bone (1985) Lancaster, pp. 321-331. , Priest ND, editor. MTT; Kusec, R., Nikolic, V., Hancevic, J., Davila, S., Alkovic, V., Trace elements in periosteal callus and cortical bone after plating for fracture (1990) Periodicum Biologorum, 92 (3), pp. 325-327; Betts, F., Wright, T., Salvati, E.A., Boskey, A., Mansal, M., Cobalt alloy metal debris in periarticular tissues from total hip revision arthoplasties (1992) Clin Orthop, 278, pp. 75-82; Brien, W.W., Salvati, E.A., Betts, F., Metal levels in cemented total hip arthroplasty: A comparison of well-fixed and loose implants (1992) Clin Orthop, 276, pp. 66-74
Keywords: Absorption spectroscopy; Animals; article; atomic absorption spectrometry; Biomaterials; bone mineralization; Calcification, Physiologic; Calcium; Cell culture medium; Cells, Cultured; Chromium; Culture Media; culture medium; Diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy; electrochemistry; Energy dispersive spectroscopic analysis; Fourier transform infrared spectroscopy; Hydrogen-Ion Concentration; infrared spectroscopy; Iron; Magnesium; Metals; microelectrode; Microelectrodes; Nickel; nonhuman; osteoblast; Osteoblast cells; Osteoblasts; pH effects; phosphorus; precipitation; Precipitation (chemical); priority journal; Rabbits; Scanning electron microscopy; Spectrophotometry, Atomic; Spectroscopic techniques; Spectroscopy; Stainless steel; supernatant; Supernatants; Tissue culture; X ray analysis; X ray dispersive analysis

In vitro testing of surface-modified biomaterials - Leitão, E.; Barbosa, M.A.; De Groot, K. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1998)
The influence of surface modification treatments such as ion implantation and sputter coating on an in vitro rat bone-marrow cell culture was studied by scanning electron microscopy and X-ray microanalysis. 316 L stainless steel, Ti-6Al-4V and Ti-5Al-2.5Fe were nitrogen ion-implanted with three fluences: 10 15, 10 16 and 10 17 ion cm
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008896106994Language of Original Document: EnglishCorrespondence Address: Leitao, E.; INEB-Instituto Engenharia Biomedica, FEUP-Faculdade de Engenharia, Universidade do Porto, Praca Coronel Pacheco 1, 4050 Porto, Portugal; email: eleitao@fsl.ho.man.ac.ukChemicals/CAS: calcium, 7440-70-2; carbon, 7440-44-0; nitrogen, 7727-37-9; stainless steel, 12597-68-1Tradenames: 316 L, aubert and duval; Thermanox; Ti-5Al-2.5Fe, deutsch titan; Ti-6Al-4V, deutsch titanManufacturers: aubert and duval; deutsch titanReferences: Kirkpatrick, C.J., Mittermayer, C., (1990) J. Mater. Sci. Mater. Med., 1, p. 9;Van Loon, J., (1995), PhD thesis, University of Leiden, The NetherlandsLi, P., De Groot, K., (1991) J. Mater. Sci. Mater. Med., 2, p. 125; Davies, J.E., (1990) Handbook of Bioactive Ceramics, 1, pp. 1-65. , edited by T. Yamamuro et al., CRC Press, Boca Raton, FL; Davies, J.E., Ottensmeyer, P., Shen, X., Hashimoto, M., Peel, S.A.F., (1991) Proceedings of the Bone Biomaterial Interface Workshop, pp. 214-228. , edited by J. E. Davies University of Toronto Press, Toronto; Gristina, A.G., Naylor, P., Myrvik, Q., (1988) Med. Progr. Through Technol., 14, p. 205; Kirkpatrick, C.J., Otterbach, T., Ander-Heiden, D., Schifer, J., Richter, H., Höcker, H., Mittermayer, C., Dekker, A., (1992) Cells Mater., 2, p. 169; Howlett, C.R., Evans, M.D.M., Wildish, K.L., Kelly, J.C., Fisher, L.R., Francis, G.W., Best, D.J., (1993) Clin. Mater., 14, p. 57; Howlett, C.R., Zreiqat, H., O'Dell, R., Noorman, J., Evans, P., Dalton, B.A., McFarland, C., Steele, J.G., (1994) J. Mater. Sci. Mater. Med., 5, p. 715; Lee, J.-S., Kaibara, M., Iwaki, M., Sasabe, H., Suzuki, Y., Kusakabe, M., (1993) Biomaterials, 14, p. 958; Röstlund, T., Thomsen, P., Bjursten, L.M., Ericson, L.E., (1990) J. Biomed. Mater. Res., 24, p. 847; Johansson, C.B., Lausmaa, J., Röstlund, T., Thomsen, P., (1993) J. Mater. Sci. Mater. Med., 4, p. 132; Harmand, M.-F., Naji, A., Gonfrier, P., (1994) Clin. Mater., 15, p. 281; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Vrouwenvelder, W.C.A., De Groot, C.G., De Groot, K., (1993) J. Biomed. Mater. Res., 27, p. 465; Puleo, D.A., Holleran, L.A., Doremus, R.H., Bizios, R., (1991) J. Biomed. Mater. Res., 25, p. 711; Davies, J.E., Lowenberger, B., Shiga, A., (1990) J. Biomed. Mater. Res., 24, p. 1289; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1993) Cells Mater., 3, p. 407; Gaillard, M.L., (1995), PhD thesis, University of Leiden, The NetherlandsRadder, A.M., Davies, J.E., Leenders, H., Van Blitterswijk, C.A., (1994) J. Biomed. Mater. Res., 28, p. 269; Shen, X., Roberts, E., Peel, S.A.F., Davies, J.F., (1993) Cells Mater., 3, p. 257; Gomi, K., Davies, J.E., (1993) J. Biomed. Mater. Res., 27, p. 429; De Bruijn, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1992) J. Biomed. Mater. Res., 26, p. 1365; Orr, R.D., De Bruijn, J.D., Davies, J.E., (1992) Cells Mater., 2, p. 241
Keywords: animal cell; animal tissue; article; biomaterial; Biomaterials; bone marrow culture; Calcium; Carbon; Cell culture; cell suspension; collagen fiber; extracellular matrix; implantation; in vitro study; In vitro testing; Ion implantation; male; materials testing; mineralization; morphology; nitrogen; nonhuman; priority journal; rat; Scanning electron microscopy; Sputtering; Stainless steel; Titanium alloys; Titanium aluminum iron alloy; Titanium aluminum vanadium alloy; X ray analysis; X ray microanalysis

New starch-based thermoplastic hydrogels for use as bone cements or drug-delivery carriers - Pereira, C.S.; Cunha, A.M.; Reis, R.L.; Vázquez, B.; San Román, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1998)
The development of new biodegradable hydrogels, based on corn starch/cellulose acetate blends, produced by free-radical polymerization with methyl methacrylate monomer (MMA) and/or an acrylic acid monomer (AA), is reported. The polymerization was initiated by a redox system consisting of a benzoyl peroxide and 4-dimethlyaminobenzyl alcohol at low temperature. These hydrogels may constitute an alternative to the materials currently used as bone cements or drug-delivery carriers. Swelling studies were carried out, as a function of pH and temperature, in buffered solutions. The xerogels were further characterized by Fourier transform-infrared spectroscopy. Tensile and compression tests, and dynamic mechanical thermal analysis were used to assess the mechanical performance of the developed materials. The fracture surfaces were observed by scanning electron microscopy. The developed materials are sensitive to the pH, showing a clear reversible transition in a relatively narrow interval of pH, which is just in the range of physiological conditions. These properties make the materials developed in this study very promising for biomedical applications. Fickian-type diffusion is the mechanism predominant in these systems, except for the composition with a higher concentration of AA, that corresponds to the most desirable kinetical behavior for controlled release (case II-transport mechanism). Furthermore, the results obtained in the mechanical tests are in the range of those reported for typical PMMA bone cements, showing that it is possible to develop partially degradable cements with an adequate mechanical behavior.
Cited By (since 1996): 67Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1008944127971Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; INEB-Inst for Biomedical Engineering, Biomaterials Laboratory, Rua do Campo Alegre 823, 4150 Porto, Portugal; email: rgreis@fe.up.ptChemicals/CAS: acrylic acid, 10344-93-1, 79-10-7; alcohol, 64-17-5; benzoyl peroxide, 94-36-0; cellulose acetate, 9004-35-7; poly(methyl methacrylate), 39320-98-4, 9008-29-1; starch, 9005-25-8, 9005-84-9Tradenames: AA, Merck, Germany; BPO, Merck, Germany; Master-Bi Y101U, novamont, Italy; MMA, Merck, GermanyManufacturers: Merck, Germany; novamont, ItalyReferences: Peppas, N.A., Mikos, A.G., (1988) Hydrogels in Medicine and Pharmacy-Fundamentals, 1, p. 1. , edited by N. A. Peppas CRC Press, Boca Raton, FL;Netti, P.A., Shelton, J.C., Revell, P.A., Pirie, C., Smith, S., Ambrosio, L., Nicolais, L., Bonfield, W., (1993) Biomaterials, 14, p. 1098; Woerly, S., (1993) Biomaterials, 14, p. 1056; Peppas, N.A., (1996) Biomaterials Science an Introduction to Materials in Medicine-Part I, p. 60. , edited by B. D. Ratner, A. S. Hoffman, F. J. Schoen and J. E. Lemons Academic Press, London; Pascual, B., Castellano, I., Vázquez, B., Gurruchaga, M., Goñi, I., (1996) Polymer, 37, p. 1005; Mack, E.J., Okano, T., Kim, S.W., (1988) Hydrogels in Medicine and Pharmacy-Polymers, 2, p. 65. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Karadag, E., Saraydin, D., Çetinkaya, S., Guven, O., (1996) Biomaterials, 17, p. 67; Kim, S.W., Bae, Y.H., Okano, T., (1992) Pharmaceut. Res., 9, p. 283; Blanco, M.D., García, O., Trigo, R.M., Teijon, J.M., Katime, I., (1996) Biomaterials, 17, p. 1061; Abusafieh, A., Siegler, S., Kalidingi, S.R., (1997) J. Biomed. Res., 38, p. 314; Norman, T.L., Kish, V., Blaha, J.D., Gruen, T.A., Hustosky, K., (1995) J. Biomed. Mater. Res., 29, p. 495; Yang, J., (1997) Biomaterials, 18, p. 1293; Lewis, G., Nyman, J.S., Trieu, H.H., (1997) J. Biomed. Mater. Res., 38, p. 221; Lewis, G., (1997) J. Biomed. Mater. Res., 38, p. 155; Domb, A.J., Manor, N., Elmalak, O., (1996) Biomaterials, 17, p. 411; Kost, J., Langer, R., (1988) Hydrogels in Medicine and Pharmacy-Properties and Applications, 3, p. 95. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Lohmann, D., (1995) Macromol. Symp., 100, p. 25; Ogawa, Y., (1997) J. Biomater. Sci. Polymer Edn, 8, p. 391; Di Silvio, L., Gurav, N., Kayser, M.V., Braden, M., Downes, S., (1994) Biomaterials, 15, p. 931; Andreopoulos, A.G., (1994) Clin. Mater., 15, p. 691; Langer, R., (1995) MRS Bull., p. 18; Heller, J., (1996) Applications of Materials in Medicine and Dentistry-Part II, p. 346. , edited by B. D. Ratner, A. S. Hoffman, F. J. Schoen and J. E. Lemons Academic Press, London; Bastioli, C., (1994) Recycle'94 - Davos Global Forum and Exposition, , Switzerland, March; Bastioli, C., (1995) Degradadble Polymers-Principles and Applications, p. 112. , Chapman and Hall, London; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) Polym. Adv. Technol., 7, p. 784; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int., 43, p. 347; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1997) Adv. Poly. Technol., 16, p. 263; Reis, R.L., Cunha, A.M., Bevis, M.J., (1997) Med. Plast. Biomateri., p. 46; Pereira, C.S., Gomes, M.E., Reis, R.L., Cunha, A.M., (1998) Foams, Emulsion and Cellular Materials, , edited by J. F. Sadoc and N. River NATO/ASI series, Kluwer Press, Dordrecht, in press; Reis, R.L., Cunha, A.M., (1998) Antec'98-Plastics on My Mind, , Society of Plastics Engieers, Atlanta, April/May in press; Reis, R.L., Cunha, A.M., (1998) Antec'98-Plastics on My Mind; Elvira, C., Levenfeld, B., Vázquez, B., San Román, J., (1996) J. Polym. Sci. A Polym. Chem., 34, p. 2783; Liso, P.A., Vázquez, B., Rebuelta, M., Hernáhz, M.L., Rotger, R., San, J., (1997) Biomaterials, 18, p. 15; Vázquez, B., Elvira, C., Levenfeld, B., Pascual, B., Goñi, I., Gurruchaga, M., Ginerba, M.P., San Róman, J., (1997) J. Biomed. Mater. Res., 34, p. 129; Vázquez, B., Elvira, C., San Román, J., Levenfeld, B., (1997) Polymer, 38, p. 4365; Castellano, I., Pascual, B., Vázquez, B., Goñi, I., Gurrruchaga, M., (1994) J. Appl. Polym. Sci., 54, p. 577; Jane, J., (1995) J.M.S. Pure Appl. Chem., A32, p. 751; Peppas, N.A., Korsmeyer, R.W., (1988) Medicine and Pharmacy-Properties and Applications, 3, p. 109. , edited by N. A. Peppas CRC Press, Boca Raton, FL; Saha, S., Pal, S., (1984) J. Biomed. Mater. Res., 18, p. 435; Lautenschlager, E.P., Moore, B.K., Schoenfeld, C.M., (1974) J. Biomed. Mater. Res. Symp., p. 185; Migiaresi, C., Fambri, L., Kolanik, J., (1994) Biomaterials, 15, p. 875; Topoleski, L.D.T., Ducheyne, P., Cuckler, J.M., (1993) Biomaterials, 14, p. 1165; Clarke, R.L., (1989) Biomaterials, 10, p. 494
Keywords: acrylic acid; alcohol; article; benzoyl peroxide; Biodegradation; bone cement; buffer; cellulose acetate; compression; Diffusion; drug delivery system; dynamics; fracture; free radical; hydrogel; infrared spectroscopy; Kinetics; low temperature; mechanical stress; oxidation reduction reaction; pH; poly(methyl methacrylate); Polymerization; priority journal; Scanning electron microscopy; Starch; tensile strength; Thermal analysis

Objective computerized fetal heart rate analysis - Bernardes, J.; Ayres-de-Campos, D.; Costa-Pereira, A.; Pereira-Leite, L.; Garrido, A. (International Journal of Gynecology and ObstetricsInt. J. Gynecol. Obstet., 1998)
Objective: To assess the validity of a computerized methodology for cardiotocogram analysis based on a recently described reproducible visual estimation of the baseline. Methods: Forty-two antepartum and 43 intrapartum cardiotocograms (CTGs) acquired by a personal computer were selected. Antepartum tracings were performed in the 48 h that preceded an elective cesarean section, and intrapartum tracings were performed until delivery. FHR baselines were estimated by an expert, according to an objective and reproducible methodology. Using these baselines, automated detection of accelerations and decelerations and estimation of variability was performed by the personal computer. A quantitative adaptation of the FIGO guidelines for fetal monitoring was used to classify tracings. Perinatal outcome was classified according to the Apgar score and umbilical arterial pH. Validity was then assessed by the proportions of agreement (PA), kappa statistic (κ), sensitivity and specificity, with 95% confidence intervals (95% CI). Cases showing a disagreement between CTG and perinatal classification were reviewed and an adjustment in baseline definition was tested. Results: The initial overall PA and κ between CTG and perinatal classification were, respectively, 0.79 (95% CI: 0.69-0.87) and 0.62 (95% CI: 0.41-0.83). The overall PA and κ, after baseline adjustment were, respectively, 0.89 (95% CI: 0.81-0.95) and 0.78 (95% CI: 0.58-0.98). Sensitivities and specificities ranged between 79% (95% CI: 60-92%) and 100% (95% CI: 95-100%). Conclusions: Good clinical prediction may be possible with an objective methodology for cardiotocogram analysis based on a recently described reproducible baseline estimation.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: IJGOAdoi: 10.1016/S0020-7292(98)00079-4PubMed ID: 9749885Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Departmento Ginecologia Obstetricia, Faculdade Medicina-Hospital S. Joao, Porto, Portugal; email: sisporto@mail.telepac.ptReferences: Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57 (1), pp. 33-37;Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., Pereira-Leite, L., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Grant, A., Principles for clinical evaluation of methods of perinatal monitoring (1984) J Perinat Med, 12, pp. 227-231; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., Van Geijn, H.P., The Porto System (1994) A Critical Appraisal of Fetal Surveillance, pp. 315-324. , In: van Geijn HP, Copray FJA, editors. Amsterdam: Elsevier Science; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring. FIGO news (1987) Int J Gynaecol Obstet, 25, pp. 159-167; Mohide, P., Grant, A., Evaluating diagnosis and screening during pregnancy and childbirth (1989) Effective Care in Pregnancy and Childbirth, pp. 66-80. , In: Chalmers I, Enkin M, Keirse M JNC, editors. Oxford University Press; Garcia-Romero, H., Garcia-Barrios, C., Ramos-Gutierrez, F.R., Effects of uncertain results on sensitivity and specificity of diagnostic tests (1996) Lancet, 348, pp. 1745-1746; Grant, J.M., The fetal heart rate is normal, isn't it?. Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Guzman, E., Vintzileos, A., Martins, M., Benito, C., Houlihan, C., The efficacy of individual computer heart rate indices in detecting acidemia at birth in growth-restricted fetuses (1996) Obstet Gynecol, 87, pp. 969-974; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Chung, T.K.H., Mohajer, M.P., Yang, Z.J., Chang, A.M.Z., Sahota, D.S., The prediction of fetal acidosis at birth by computerized analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Stigsby, B., Nielson, P.V., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. I. Methods of data reduction and diagnostic procedure (1988) Acta Obstet Gynecol Scand, 67, pp. 455-460
Keywords: Apgar score; arterial pH; article; Cardiotocography; cesarean section; computer analysis; Computerized analysis; Female; Fetal heart rate; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Processing, Computer-Assisted; practice guideline; Predictive Value of Tests; Pregnancy; priority journal; umbilical artery; validity

Semiautomated ultrasonographic measurement of fetal nuchal translucency using a computer software tool - Bernardino, F.; Cardoso, R.; Montenegro, N.; Bernardes, J.; Marques de Sá, J. (Ultrasound in Medicine and BiologyUltrasound Med. Biol., 1998)
Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic fines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.Nuchal translucency (NT) thickness measurement has been recently proposed as a part of routine ultrasound scanning during the late first trimester of pregnancy, for the early screening of chromosomal abnormalities. Manual determination of NT is currently performed using electronic callipers placed by the operator in the middle of two echogenic lines displayed on the screen. Therefore, intraobserver and interobserver repeatability can be questioned. This paper presents a software tool that has been developed for achieving this goal in a semiautomatic way, improving the reproducibility of the method.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: USMBAdoi: 10.1016/S0301-5629(97)00235-4PubMed ID: 9483771Language of Original Document: EnglishCorrespondence Address: Marques De Sa, J.; Instituto de Engenharia Biomedica, Pt. Coronel Pacheco 1, P-4050 Porto, Portugal; email: jmsa@garfield.fe.up.ptTradenames: Microsoft Visual C++, microsoft, United StatesManufacturers: microsoft, United StatesReferences: Jain, A.K., (1982) Fundamentals of Digital Image Processing, , New York: Prentice Hall International Editions;Neilson, J., Grant, A., Ultrasound in pregnancy (1989) A Guide to Effective Care in Pregnancy and Childbirth., pp. 48-56. , Enkin M, Keirse MJN, Chalmers I. eds. New York, London: Oxford University Press; Nicolaides, K.H., Azar, G., Byrne, D., Mansur, C., Marks, K., Fetal nuchal translucency: Ultrasound screening for chromosomal detects in first trimester of pregnancy (1992) BMJ, 304, pp. 867-869; Pandya, P.P., Brizot, M.L., Kuhn, P., Snijders, R.J.M., Nicolaides, K.H., First trimester fetal nuchal translucency thickness and risk for trisomies (1994) Obstet Gynecol, 84, pp. 420-423; Pandya, P.P., Kondylios, A., Hilbert, L., Snijders, R.J.M., Nicolaides, K.H., Chromosomal defects and outcome in 1015 fetuses with increased nuchal translucency (1995) Ultrasound Obstet Gynecol, 5, pp. 15-19; Pandya, P.P., Altman, D.G., Brizot, M.L., Pettersen, H., Nicolaides, K.H., Repeatability of measurement of fetal nuchal translucency thickness (1995) Ultrasound Obstet Gynecol, 5, pp. 334-337; Roberts, L.J., Bewley, S., Mackinson, A.M., Rodeck, C.H., First trimester fetal nuchal translucency: Problems of screening the general population (1995) Br J Obstet Gynaecol, 102, pp. 381-385; Zador, I.E., Salari, V., Sokol, R.J., Computer applications in fetal medicine (1994) The Fetus As A Patient, pp. 117-124. , Kurjak A, Chervenak FA, eds. London/ New York: Parthenon Publ
Keywords: article; cervical spine; chromosome aberration; Chromosome Aberrations; Chromosome Disorders; Computer aided diagnosis; computer program; Computer software; computer system; Female; Fetal monitoring; Fetal nuchal translucency; fetus echography; first trimester pregnancy; Humans; Image analysis; Image Processing, Computer-Assisted; Image thresholding; Medical imaging; Neck; observer variation; Pregnancy; Pregnancy Trimester, First; priority journal; reproducibility; Reproducibility of Results; Software; Software package NUCA; Thickness measurement; Ultrasonic imaging; Ultrasonography, Prenatal; ultrasound

Adsorptive Stripping Voltammetric Measurements of Chromium Accumulation in Mice Organs Using Mercury Film Microelectrodes - Pereira, M.C.; Pereira, M.L.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Chromium is the metallic species of most concern with the use of stainless steel implants. To study the distribution of chromium in mice organs with time, several animals were subcutaneously injected with 2.70 × 10
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomédica, Depto. de Engenharia Química, Universidade do Porto, Praça do Coronel Pacheco, 1, P-4050 Porto, PortugalReferences: Katz, S.A., Salem, H., (1994) The Biological and Environmental Chemistry of Chromium, , VCH, Weinheim ch. 5;Black, J., (1988) J. Bone Joint Surg., 70 B, p. 517; Minski, M.J., Dobbs, H.S., (1980) Trace Element Analytical Chemistry in Medicine and Biology, p. 339. , (Eds: P. Bratter, P. Schramel), Walter de Gruyter, Berlin; Bartolozzi, A., Black, J., (1985) Biomaterials, 6, p. 2; Merritt, K., Fedele, C.D., Brown, S.A., (1992) Biomaterial-Tissue Interfaces, p. 10. , (Eds: P.J. Doherty et al), Elsevier, Amsterdam; Merritt, K., Brown, S.A., (1995) J. Biomed. Mater. Res., 29, p. 627; Katz, S.A., Salem, H., (1993) J. Appl. Toxicology, 13, p. 217; Polak, J.L., Turk, J., Frey, R., (1973) Prog. Allergy, 17, p. 145; Standeven, A.M., Wetterhahn, K.E., (1991) Chem. Res. Toxicol., 4, p. 616; Anderson, R.A., (1989) Sci. Total Environ., 86, p. 75; Lugowski, S., Smith, D.C., Van Loon, J.C., (1987) J. Biomed. Mater. Res., 21, p. 657; Subramanian, K.S., (1989) Metabolism of Minerals and Trace Elements in Human Disease, , (Eds: M. Abdulla et al), Smith-Gordon ch. 28; Minami, H., Zhang, Q., Itoh, H., Atsuya, I., (1994) Microchemical J., 49, p. 126; Veillon, C., Patterson, K.Y., Bryden, N.A., (1982) Clin. Chem., 28, p. 2309; Golimowski, J., Valenta, P., Nurnberg, H.W., (1985) Fresenius Z. Anal. Chem., 322, p. 315; Boussemart, M., Van Den Berg, C.M.G., Ghaddaf, M., (1992) Anal. Chim. Acta, 262, p. 103; Wang, J., Lu, J., Olsen, K., (1992) Analyst, 117, p. 1913; Olsen, K.B., Wang, J., Setiadji, R., Lu, J., (1994) Environ. Sci. Technol., 28, p. 2074; Pereira, M.C., Faria, J.L., Reis, M.L., Sousa, J.P., (1997) Electroanalysis, 9, p. 1; Pereira, M.C., Sousa, J.P., (1996) Portug. Electrochem. Acta, 14, p. 273; Pereira, M.C., Sousa, J.P., (1995) Portug. Electrochem. Acta, 13, p. 477; Miller, J.N., (1992) Analyst, 117, p. 1913; Van Den Berg, C.M.G., (1991) Anal. Chim. Acta, 250, p. 265; Merritt, K., Crowe, T.D., Brown, S.A., (1989) J. Biomed. Mater. Res., 23, p. 845; Yang, J., Black, J., (1989) Biomaterials, 23, p. 845; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci: Mater. Med., 6, p. 523
Keywords: Adsorptive stripping voltammetry; Biomaterials; Chromium; Microelectrodes

Apatite deposition on titanium surfaces - The role of albumin adsorption - Serro, A.P.; Fernandes, A.C.; Saramago, B.; Lima, J.; Barbosa, M.A. (BiomaterialsBIOMATERIALS, 1997)
Titanium implant surfaces are known to spontaneously nucleate apatite layers when in contact with simulated body fluids. However, adsorption of proteins may influence the process of apatite layer formation. In this study the role of bovine serum albumin (BSA) adsorption in the process of apatite deposition on titanium substrates is investigated. Deposition of calcium phosphate was induced by immersing titanium substrates in a Hank's balanced salt solution (HBSS) for times ranging from 1 to 23 days. The resulting substrates were studied by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), wettability measurements and electrochemical impedance determinations. All these methods indicate the presence of a calcium phosphate layer. The same procedure was repeated substituting HBSS with a solution of BSA in HBSS. Although SEM, EDS and electrochemical impedance spectra do not reveal the presence of an apatite layer, XPS analysis strongly indicates that the inhibition of apatite formation by BSA is only partial. The competition between BSA adsorption and apatite deposition seems to lead to a mixed film where the protein co-exists with calcium phosphate. Wettability studies suggest that this surface film is heterogeneous and porous, similar to the thicker films formed in albumin-free HBSS.Titanium implant surfaces are known to spontaneously nucleate apatite layers when in contact with simulated body fluids. However, adsorption of proteins may influence the process of apatite layer formation. In this study the role of bovine serum albumin (BSA) adsorption in the process of apatite deposition on titanium substrates is investigated. Deposition of calcium phosphate was induced by immersing titanium substrates in a Hank's balanced salt solution (HBSS) for times ranging from 1 to 23 days. The resulting substrates were studied by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), wettability measurements and electrochemical impedance determinations. All these methods indicate the presence of a calcium phosphate layer. The same procedure was repeated substituting HBSS with a solution of BSA in HBSS. Although SEM, EDS and electrochemical impedance spectra do not reveal the presence of an apatite layer, XPS analysis strongly indicates that the inhibition of apatite formation by BSA is only partial. The competition between BSA adsorption and apatite deposition seems to lead to a mixed film where the protein co-exists with calcium phosphate. Wettability studies suggest that this surface film is heterogeneous and porous, similar to the thicker films formed in albumin-free HBSS.
Cited By (since 1996): 72Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(97)00031-8PubMed ID: 9212191Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Quimica Estrutural, Complexo I, Instituto Superior Tecnico, Av. Rovisco Pais, 1096 Lisboa Codex, PortugalChemicals/CAS: alpha-tricalcium phosphate; Apatites; calcium phosphate, 10103-46-5; Calcium Phosphates; dicalcium phosphate anhydrous, 7757-93-9; Hanks Balanced Salt Solution; Isotonic Solutions; monocalcium phosphate; Serum Albumin, Bovine; tetracalcium phosphate; Titanium, 7440-32-6References: Sundgren, J.-E., Bodo, P., Lundstrom, I., Auger electron spectroscopic studies of the interface between human tissue and implants of titanium and stainless steel (1986) J. Colloid Interface Sci., 10, pp. 9-20;Hanawa, T., Ota, M., Characterization of surface film formed on titanium in electrolyte using XPS (1992) Appl. Surface Sci., 55, pp. 269-276; Sousa, S.R., Barbosa, M.A., Corrosion resistance of titanium cp in saline physiological solutions with calcium phosphate and proteins (1993) Clin. Mater., 14, pp. 287-294; Li, P., Ohtsuki, C., Kokubo, T., Nakanishi, K., Soga, N., De Groot, K., The role of hydrated silica, titania and alumina in inducing apatite on implants (1994) J. Biomed. Mater. Res., 28, pp. 7-15; Tanahashi, M., Yao, T., Kokubo, T., Apatite coating on organic polymers by a biomimetic process (1994) J. Am. Ceram. Soc., 77, pp. 2805-2808; Martin, R.I., Brown, P.W., Formation of hydroxy-apatite in serum (1994) J. Mater. Sci.: Mater. Med., 5, pp. 96-102; Malmsten, M., Ellipsometric studies of protein layers adsorbed at hydrophobia surfaces (1994) J. Colloid Interface Sci., 166, pp. 333-342; Oscarsson, S., Protein adsorption onto protein-covered silica-gels (1994) J. Colloid Interface Sci., 165, pp. 402-410; Baier, R.E., Meyer, J.R., Natella, R.R., Carter, J.M., Surface properties determine bioadhesive outcomes: Methods and results (1984) J. Biomed. Mater. Res., 18, pp. 337-355; Andrade, J.D., (1985) Surface and Interfacial Aspects of Biomedical Polymers, 2, pp. 1-80. , ed. J. D. Andrade. Plenum Press, New York; Van Der Vegt, W., Van Der Mei, H.C., Busscher, H.J., Interfacial free energies in protein solution droplets on FEP-Teflon by axisymmetric drop shape analysis by profile - IgG versus BSA (1993) J. Colloid Interface Sci., 156, pp. 129-136; Kipaldi, V.D., Lemons, J.E., Surface energy characterization of unalloyed titanium (1994) J. Biomed. Mater. Res., 28, pp. 1419-1425; Van Der Vegt, W., Van Der Mei, H.C., Busscher, H.J., A comparison of different approaches to calculate surface free energy of protein-coated substrata from measured contact angles of liquids (1994) Langmuir, 10, pp. 1314-1318; Cheng, P., Li, D., Boruvka, L., Rotenberg, Y., Neumann, A.W., Automation of axisymmetric drop shape analysis for measurements of interfacial tensions and contact angles (1990) Colloids Surfaces, 43, pp. 151-167; Cheng, P., Neumann, A.W., Computational evaluation of axisymmetric drop shape analysis - Profile (ADSA-P) (1992) Colloids Surfaces, 62, pp. 297-306; Barbosa, M.A., Electrochemical impedance studies on calcium phosphate-metal interfaces (1991) Bioceramics, 4, pp. 325-333. , ed. W. Bonfield, G. W. Hastings and K. E. Tanner. Butterworth-Heinemann, London; Ström, G., Carlsson, G., Wettability of kraft pulps -Effect of surface composition and oxygen plasma treatment (1993) Contact Angle, Wettability and Adhesion, pp. 475-491. , ed. K. L. Mittal. VSP, Utrecht; Good, G.R., Contact angle, wetting, and adhesion: A critical review (1992) J. Adhesion Sci. Technol., 6, pp. 1269-1302; Gomes, C.M., Fernandes, A.C., Almeida, B.S., The surface tension of cork from contact angle measurements (1993) J. Colloid Interface Sci., 156, pp. 195-201; Van Oss, C.J., Good, R.J., Chaudhury, M.K., The role of van der Waals and hydrogen bonds in hydrophobic interactions between biopolymers and low energy surfaces (1986) J. Colloid Interface Sci., 111, pp. 378-390; Absolom, D.R., Van Oss, C.J.A., Neumann, A.W., Determination of surface tensions of proteins. II. Surface tension of serum albumin, altered at the protein-air interface (1981) Biochim. Biophys. Acta, 670, pp. 74-78; Paynter, R.W., Ratner, B., The study of interfacial proteins and biomolecules by X-ray photoelectron spectroscopy (1985) Surface and Interfacial Aspects of Biomedical Polymers, 2, pp. 189-216. , ed. J. D. Andrade. Plenum Press, New York; Raider, S.I., Flitsch, R., Palmer, M.J., Oxide growth on etched silicon in air at room temperature (1975) J. Electrochem. Soc.: Solid State Sci. Technol., 122, pp. 413-418
Keywords: Adsorption; Albumin; Albumin adsorption; Animals; Apatite; Apatite deposition; Apatites; article; Binding Sites; Bovinae; bovine serum albumin; Calcium Compounds; calcium phosphate; Calcium phosphates; Cattle; Deposition; Electric Impedance; Electrochemical impedance; Energy dispersive spectroscopy; impedance; implant; Isotonic Solutions; Microscopy, Electron, Scanning; priority journal; Prostheses and Implants; Proteins; Scanning electron microscopy; Serum Albumin, Bovine; Spectrometry, X-Ray Emission; Substrates; Surface Properties; surface property; Surfaces; Tissue Preservation; Titanium; wettability; X ray photoelectron spectroscopy

Dissolution and deposition processes at metal/apatite interfaces - Barbosa, M.A. (Anales de Quimica, 1997)
The coating of implant surfaces with an apatite layer has become one of the most widely used methods to improve bonding to bone. The metal/apatite interface is, however, a region of chemical and mechanical weaknesses, which led some Authors to cast doubts on the long-term integrity of apatite coated implants. These concerns arc essentially related to coatings obtained by conventional plasma-spraying techniques. Recently, there have been attempts to produce coatings with better properties, particularly by acting at the surface preparation stages and by using alternative methods of deposition. Apatite deposition in a liquid phase is one of the new routes being explored. This paper attempts to focus on the main chemical processes involved in the stability of the metal/apatite interface, in order to establish the basic principles for further technological developments. © Springer-Verlag Ibérica 1997.

Electrochemical and surface modifications on N +-ion implanted Ti-5Al-2.5Fe immersed in HBSS - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Corrosion ScienceCorros. Sci., 1997)
The electrochemical behaviour of nitrogen ion-implanted Ti-5Al-2.5Fe was studied in HBSS-Hank's balanced salt solution, by open-circuit potential vs time and cyclic polarization techniques. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. All ion-implanted surfaces showed higher corrosion resistance than the non-implanted ones. The corrosion potential of the ion-implanted samples was more noble and their passivation current was lower than the non-implanted ones. X-ray photo-electron spectroscopy showed that the immersion of Ti-5Al-2.5Fe in HBSS produces a Ca- and P-rich surface layer. © 1997 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 21Export Date: 21 November 2012Source: ScopusCODEN: CRRSALanguage of Original Document: EnglishCorrespondence Address: Leitão, E.; INEB - Inst. de Engenharia Biomedica, Praça do Coronel Pacheco, 1, 4050, Porto, PortugalReferences: Tengvall, P., Lundström, I., (1992) Clinical Mater., 9, pp. 115-134;Seah, K.H.W., Chen, X., (1993) Corros. Sci., 34 (11), pp. 1841-1851; Sutherland, D.S., Forshaw, P.D., Allen, G.C., Brow, I.T., Williams, K.R., (1993) Biomaterials, 14 (12), pp. 893-899; Kasemo, B., (1983) J. of Prosthetic Dentistry, 49 (6), pp. 832-837; Ducheyne, P., Radin, S., Ishikawa, K., (1992) Bone-bonding Biomaterials, pp. 213-218. , edited by P. Ducheyne, T. Kokubo and C.A. van Blitterswijk, (Reed Heathcare Communications); Sundgreen, J.-E., Bodö, P., Lundström, I., (1986) J. Colloid Interface Sci., 110, pp. 9-20; Hanawa, T., Ota, M., (1991) Biomaterials, 12, pp. 767-774; Leitão, E., Barbosa, M.A., De Groot, K., (1995) J. Mater. Sci.: Mater. in Med., 6, pp. 849-852; Pavlov, P.V., (1983) Nucl. Inst. Meth. Phys. Res., 209-210, pp. 791-798; Sioshansi, P., (1984) Thin Solid Films, 118, pp. 61-71; Bernard, F., Dupuy-Philon, J., Bert, J., Remy, D., Meyer, B., Besse, J.L., (1995) Advances in Mater. Sci. and Implant Orthop. Surgery, pp. 195-206. , edited by R. Kossowsky and N. Kossovsky; Leitão, E., Sá, C., Silva, R.A., Barbosa, M.A., Ali, H., (1995) Corros. Sci., 37 (11), pp. 1861-1866; Hohmuth, K., Rauschenbach, B., (1985) Mater. Sci. Eng., 69, pp. 489-499; Rauschenbach, B., Kolitsch, A., (1983) Phys. Stat. Sol (A), 80, pp. 211-222; Rauschenbach, B., Kolitsch, A., Hohmuth, K., (1983) Phys. Stat. Sol (A), 80, pp. 471-482; Rauschenbach, B., (1991) Nucl. Inst. Meth. Phy. Res., B53, pp. 35-45; Dos Santos, C.A., Behar, M., De Souza, J.P., Baumvol, I.J.R., (1983) Nucl. Instrum. Methods, 209-210, pp. 907-912; Helmig, K., Rauschenbach, B., (1986) Phys. Stat. Sol. (B), 138, pp. k1-k6; Maüsli, P.A., Simpson, J.P., Burri, G., Steinemann, S.G., (1988) Advances in Biomater., 8, p. 305. , Implant Mater. In Biofunction, edited by C. de Putter, C.L. de Lange, K. de Groot and A.J.C. Lee; Maüsli, P.A., Bloch, P.R., Geret, V., Steinemann, S.G., (1986) Biological and Biomechanical Performance of Biomaterials, p. 57. , edited by P. Christel, A. Meunier and A.J.C. Lee; Sousa, S.R., Barbosa, M.A., (1993) Clinical Mater., 14, pp. 287-294; Orr, R.D., De Bruijn, J.D., Davies, J.E., (1992) Cells and Mater., 2 (3), pp. 241-245; Klein, C.A.P.T., Patka, P., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) Biomater., 15, pp. 146-150
Keywords: A. titanium alloys; B. EIS; B. XPS; C. passive films; Corrosion resistance; Cyclic polarization technique; Hank's balanced salt solution (HBSS); Ion implantation; nitrogen; Open circuit potential technique; Passivation; Passive films; Surface treatment; Titanium alloys; X ray photoelectron spectroscopy

Electrochemical and surface modifications on N +-ion-implanted 316L stainless steel - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
The effect of nitrogen-ion implantation on the electrochemical behaviour of 316L stainless steel in a simulated physiological solution (HBSS-Hank's Balanced Salt Solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing the surfaces and choosing the best nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence improves the corrosion resistance of the 316L stainless steel. The effect of nitrogen-ion implantation on the electrochemical behaviour of 316L stainless steel in a simulated physiological solution (HBSS-Hank's Balanced Salt Solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing the surfaces and choosing the best nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence improves the corrosion resistance of the 316L stainless steel.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018532900458Language of Original Document: EnglishCorrespondence Address: Leitao, E.; Instituto de Engenharia Biomedica, Praca do Coronel Pacheco 1, 4050 Porto, PortugalReferences: Seah, K.H.W., Chen, X., (1993) Corros. Sci., 34, pp. 1841-1851;Fraker, A.C., Ruff, A.W., Sung, P., Van Orden, A.C., Speck, K.M., (1983) Titanium Alloys in Surgical Implants, pp. 206-219. , ASTM STP 796, edited by H. A. Luckey and F. Kublei Jr; Nakayama, Y., Yamamuro, T., Kumar, P., Shimisu, K., Kotoura, Y., Oka, M., Kwafuku, J., Takashima, T., (1990) J. Appl. Biomater., 1, pp. 307-313; Puleo, D.A., Huh, W.W., (1995) J. Appl. Biomater., 6, pp. 109-116; Sundgreen, J.-E., Bodö, P., Lundström, I., (1986) J. Colloid Interface Sci., 110, pp. 9-20; Merrit, K., Brown, S.A., (1995) J. Biomedical Mater. Res., 29, pp. 627-633; Merrit, K., Brown, S.A., (1994) Tech Orthop., 8, pp. 228-236; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, pp. 523-527; Johansson, C.B., Lausmaa, J., Röstlund, T., Thomsen, P., (1993) J. Mater. Sci. Mater. Med., 4, pp. 132-141; Bernard, F., Dupuy-Philon, J., Bert, J., Remy, D., Moyen, B., Besse, J.L., Advances in materials science and implant orthopaedic surgery (1995) NATO-ASI Series E: Applied Science, 24, pp. 195-206. , edited by R. Kossowsky and N. Kossowsky; Rauschenbach, B., (1991) Nucl. Instrum. Methods Phys. Res., B53, pp. 35-45; Rauschenbach, B., Kolitsch, A., Hohmuth, K., (1983) Phys. Status Solidi (A), 80, pp. 471-482; Howlett, C.R., Evans, M.D.M., Wildish, K.L., Kelly, J.C., Fisher, L.R., Francis, G.W., Best, D.J., (1993) Clin. Mater., 14, pp. 57-64; Howlett, C.R., Zreiqat, H., O'Dell, R., Noorman, J., Evans, P., Dalton, B.A., Mcfarland, C., Steele, J.G., (1994) J. Mater. Sci. Mater. Med., 5, pp. 715-722; Röstlund, T., Thomson, P., Bjursten, L.M., Ericson, L.E., (1990) J. Biomed. Mater. Res., 24, pp. 847-860; Leitão, E., Sá, C., Silva, R.A., Barbosa, M.A., Ali, H., (1995) Corros. Sci., 37, pp. 1861-1866; Barbosa, M.A., (1989) Portugaliae Electrochimica Acta, 7, pp. 567-590; Rauschenbach, B., Kolitsch, A., (1983) Phys. Status Solidi (A), 80, pp. 211-222; Rauschenbach, B., (1991) Nucl. Tracks Radiat. Meus., 19, pp. 943-946; Carbucicchio, M., Bardani, L., Tosto, S., (1981) J. Appl. Phys., 52, p. 4589; Hu, W.W., Herman, H., Clayton, C.R., Kozubowski, J., Kant, R.A., Hirvonen, J.K., Maccrone, R.K., Surface related mechanical properties of nitrogen implanted 1018 steel (1979) Proc. Ion Implantation Metallurgy, p. 92. , edited by C. M. Preece and J. K. Hirvonen AIME. Warrendale, Cambridge, MA; Dos Santos, C.A., Behar, M., De Souza, J.P., Baumvol, I.J.R., (1983) Nucl. Inustrum. Methods, 209-210, pp. 907-912; Sousa, S., Barbosa, M.A., (1991) J. Mater. Sci. Mater. Med., 2, pp. 19-26; Klein, C.A.P.T., Patka, P., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) Biomaterials, 15, pp. 146-150
Keywords: article; balanced salt solution; Composition effects; Corrosion; Corrosion resistance; Cyclic polarization technique; Electrochemical corrosion; electrochemistry; implantation; Ion implantation; limb prosthesis; nitrogen; Polarization; priority journal; prosthesis failure; Simulated physiological solutions; Solutions; Stainless steel; Stainless steel 316L; Surface Properties; Surface treatment; time

Electrochemical impedance spectroscopy of nitrogen- and carbon-sputter coated 316 L stainless steel - Leitão, E.; Silva, R.A.; Barbosa, M.A. (Corrosion ScienceCorros. Sci., 1997)
The effect of nitrogen and carbon sputter coatings on the electrochemical behaviour of 316 L stainless steel in a simulated physiological solution (Hank's Balanced Salt Solution) was studied by electrochemical impedance spectroscopy with the aim of characterizing the surfaces and choosing the best coating. Coatings with different thicknesses and structures were tested. The results showed that thicker sputter coatings produce surfaces with higher charge transfer resistance and lower interface capacities. This indicates that these materials probably owe their high corrosion resistance to the formation of more protective films. © 1997 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: CRRSALanguage of Original Document: EnglishCorrespondence Address: Leitão, E.; INEB - Inst. de Engenharia Biomedica, Praça do Coronel Pacheco, 1, 4050, Porto, PortugalReferences: Gristina, A.G., Naylor, P., Myrvik, Q., (1988) Medical Progress Through Technology, 14, pp. 205-224;Gomi, K., Davies, J.E., (1993) J. Biomedical Mater. Res., 27, pp. 429-431; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford J., Jr., Dean, D.D., Boyan, B.D., (1995) J. Biomedical Mater. Res., 29, pp. 389-401; Groessner-Schreiber, B., Tuan, R.S., (1992) J. of Cell Sc., 101, pp. 209-217; Peidl, R.D., Ramp, W.K., Nicholson, N.C., Kaisinger, K.K., Harrow, M.E., (1994) 20th Annual Meeting of the Society for Biomaterials, 11. , Boston, USA; Puleo, D.A., Holleran, L.A., Doremus, R.H., Bizios, R., (1991) J. Biomedical Mater. Res., 25, pp. 711-723; Vrouwenvelder, W.C.A., Groot, C.G., De Groot, K., (1993) J. Biomedical Mater. Res., 27, pp. 465-475; Hazan, R., Oron, U., (1993) J. of Orthopaedic Res., 11, pp. 655-663; De Bruijn, J.D., Flach, J.S., De Groot, K., Van Blitterswijk, C.A., Davies, J.E., (1993) Cells and Mater., 3, pp. 2115-2127; Röstlund, T., Thomsen, P., Bjursten, L.M., Ericson, L.E., (1990) J. Biomedical Mater. Res., 24, pp. 847-860; Bard, A.J., Faulkner, L.R., (1980) Electrochemical Methods, , John Wiley and Sons; Bundy, K.J., Dillard, J., Luedemann, R., (1993) Biomaterials, 14 (7), pp. 529-536; Leitão, E., Sá, C., Silva, R.A., Barbosa, M.A., Ali, H., (1995) Corros. Sci., 37, pp. 1861-1866; Garrido, A., Leitão, E., (1992) IMPFRA-electrochemical Impedance Software, , internal publication; (1993) Project BRITE/EURAM n°0477 Internal Report; Barbosa, M.A., (1991) Bioceramics, 4, pp. 325-333. , Edited by W. Bonfield, G.W. Hastings and K.E. Tanner; Sousa, S.R., Barbosa, M.A., (1993) Clinical Materials, 14, pp. 287-294
Keywords: A. Stainless steel; B. EIS; C. passive films; Carbon; Charge transfer; Coatings; Composition effects; Corrosion resistance; electrochemistry; Films; Hank's balanced salt solution; nitrogen; Passive films; Protective coatings; sodium chloride; Spectroscopy; Sputter deposition; Stainless steel; Surface phenomena

Guided bone regeneration using osteopatite® granules and polytetrafluoroethylene membranes - Vasconcelos, M.; Afonso, A.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
Granules of a modified hydroxyapatite, Osteopatite®, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.Granules of a modified hydroxyapatite, Osteopatite, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018533217238Language of Original Document: EnglishCorrespondence Address: Vasconcelos, M.; Faculty of Dental Medicine, University of Porto, Rua Dr. Roberto Frias, 4200 Porto, PortugalTradenames: OsteopatiteReferences: Cavalheiro, J., Branco, R., Vasconcelos, M., (1991) Proceedings of the 4th International Conference on Bioceramics, p. 205. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner, London, UK Butterworth-Heinemann, Oxford;Cavalheiro, J., Vasconcelos, M., Afonso, A., Peres, F., Branco, R., (1994) Stoma, 30, p. 15; Dahlin, C., Lekholm, U., Becker, W., Becker, B., Higuchi, K., Callens, A., Steenberghe, D., (1995) Int. J. Oral Maxillofac. Implants, 3, p. 312; Aughtun, M., Doz, P., Yildirim, M., Spiekermann, H., Biesterfeld, S., (1995) Int. J. Oral Maxillofac. Implants, 4, p. 421; Simion, M., Scarano, A., Gionso, L., Piattelli, A., (1995) Int. J. Oral Maxillofac. Implants, 3, p. 312; Afonso, A., Santos, J.D., Vasconcelos, M., Branco, R., Cavalheiro, J., (1996) J. Mater. Sci: Mater. Med., 7, p. 507; Jovanovic, S.A., Schenk, R.K., Orsini, M., Kenney, E.B., (1995) Int. J. Oral Maxillofac. Implants, 1, p. 27; Sander, L., Karring, T., (1995) J. Clin. Periodontol., 22, p. 295; Grevstad, H.J., Leknes, K.N., (1993) J. Clin. Periodontol., 20, p. 193; Piattelli, A., Scarano, A., Russo, P., Matarasso, S., (1996) Biomaterials, 17, p. 791
Keywords: animal experiment; Animalia; biomaterial; Bone; bone defect; Bone Regeneration; conference paper; controlled study; haversian canal; hydroxyapatite; Implants (surgical); microscopy; nonhuman; Optical microscopy; Oryctolagus cuniculus; Phosphate minerals; politef; Polymeric membranes; Polytetrafluoroethylenes; priority journal; rabbit; tibia

Influence of substrate material and surface finishing on the morphology of the calcium-phosphate coating - Leitão, E.; Barbosa, M.A.; De Groot, K. (Journal of Biomedical Materials ResearchJ. BIOMED. MATER. RES., 1997)
The formation of an apatite-like layer was achieved by immersing Ti- 6A1-4V, Ti-A1-2.5Fe, and 316 L stainless-steel substrata in Hank's balanced salt solution (HBSS). The layer was characterized by surface analysis techniques, namely, X-ray microanalysis and X-ray diffraction, and the morphology was observed by scanning electron microscopy and atomic force microscopy. The concentrations of Ca and P were monitored as a function of time. The morphology of the precipitate layer seems to be dependent both on the type of metal substrate and its surface finish. Polished Ti-6A1-4V and Ti-A1-2.5Fe surfaces exhibit a plate precipitate morphology, whereas rougher surfaces show scattered crystal-like precipitation. The results suggest that the layer produced by immersion of polished titanium alloys in HBSS is constituted by an amorphous apatite.The formation of an apatite-like layer was achieved by immersing Ti-6Al-4V, Ti-Al-2.5Fe, and 316 L stainless-steel substrata in Hank's balanced salt solution (HBSS). The layer was characterized by surface analysis techniques, namely, X-ray microanalysis and X-ray diffraction, and the morphology was observed by scanning electron microscopy and atomic force microscopy. The concentrations of Ca and P were monitored as a function of time. The morphology of the precipitate layer seems to be dependent both on the type of metal substrate and its surface finish. Polished Ti-6Al-4V and Ti-Al-2.5Fe surfaces exhibit a plate precipitate morphology, whereas rougher surfaces show scattered crystal-like precipitation. The results suggest that the layer produced by immersion of polished titanium alloys in HBSS is constituted by an amorphous apatite.
Cited By (since 1996): 11Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199707)36:1<85::AID-JBM10>3.0.CO;2-IPubMed ID: 9212392Language of Original Document: EnglishCorrespondence Address: Leitao, E.; INEB, FEUP, Praca do Coronel Pacheco 1, 4050 Porto, PortugalChemicals/CAS: Alloys; alpha-tricalcium phosphate; Aluminum, 7429-90-5; Biocompatible Materials; calcium phosphate, 10103-46-5; Calcium Phosphates; dicalcium phosphate anhydrous, 7757-93-9; Hanks Balanced Salt Solution; Iron, 7439-89-6; Isotonic Solutions; monocalcium phosphate; Stainless Steel, 12597-68-1; tetracalcium phosphate; titanium alloy (TiAl6V4), 12743-70-3; Titanium, 7440-32-6References: Fujishiro, Y., Sato, T., Okuwaki, A., Coating of hydroxyapatite on metal plates using thermal dissociation of calcium-EDTA chelate in phosphate solutions under hydrothermal conditions (1995) Mater. Sci. Mater. Med., 6, pp. 172-176;Shirkhanzadeh, M., Calcium phosphate coatings prepared by electrocrystallization from aqueous electrolytes (1995) J. Mater, Sci. Mater. Med., 6, pp. 90-93; De Groot, K., Ceramics of calcium phosphates (1983) Bioceramics of Calcium Phosphates, p. 100. , K. de Groot (ed.), CRC Press, Boca Raton, FL; Leitão, E., Barbosa, M.A., De Groot, K., In vitro calcification of orthopaedic implant materials (1995) J. Mater. Sci. Mater. Med., 6, pp. 849-852; Ducheyne, P., Radin, S., Ishikawa, K., The rate of calcium phosphate precipitation on metal and ceramics, and the relationship to bioactivity (1992) Bone Bonding Biomaterials, pp. 213-218. , P. Ducheyne, T. Kokubo, and C. A. van Blitterswijk (eds.), Reed Heathcare Communications, The Netherlands; Li, P., (1993) In Vitro and in Vivo Calcium Phosphate Induction on Gel Oxides, , Ph.D. thesis, Leiden University; Kokubo, T., Bioactivity of glasses and glass ceramics (1992) Bone Bonding Biomaterials, pp. 31-46. , P. Ducheyne, T. Kokubo, and C. A. van Blitterswijk (eds.), Reed Healthcare Communications, The Netherlands; Kokubo, T., Tanahashi, M., Yao, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., Apatitepolymer composites prepared by biomimetic process: Improvement of adhesion of apatite to polymer by glow-discharge treatment (1993) Bioceramics, 6, pp. 327-332. , P. Ducheyne and D. Christiansen (eds.), Butterworth-Heinemann, Oxford, United Kingdom; Hanawa, T., Titanium and its oxide film: A substrate for forming apatite (1991) Proceedings of the Bone Biomaterial Interface Workshop, pp. 49-61. , Toronto, Dec., 1990, J. E. Davies (ed.), University of Toronto Press, Toronto, Canada; Hanawa, T., Ota, M., Calcium phosphate naturally formed on titanium in electrolyte solution (1991) Biomaterials, 12, pp. 767-774; Hanawa, T., Ota, M., Characterization of surface film formed on titanium in electrolyte using XPS (1992) Appl. Surface Sci., 55, pp. 269-276; Radin, S.R., Ducheyne, P., The effect of calcium phosphate ceramic composition and structure on in vivo behavior. II. Precipitation (1993) J. Biomed. Mater. Res., 27, pp. 35-45
Keywords: Alloys; Aluminum; Aluminum alloys; article; Biocompatibility; Biocompatible Materials; biomaterial; Calcium Compounds; calcium phosphate; Calcium phosphate coatings; Calcium phosphates; Coatings; Finishing; Humans; hydroxyapatite; Implants (surgical); Iron; Isotonic Solutions; materials testing; metal implantation; Microscopy, Electron, Scanning; morphology; Phosphates; Stainless steel; Surface Properties; surface property; Surface testing; Surface treatment; Time Factors; Titanium; Titanium alloys; X ray diffraction; X ray diffraction analysis

Investigation of the dissolution of the bioceramic hydroxyapatite in the presence of titanium ions using ToF-SIMS and XPS - Leadley, S.R.; Davies, M.C.; Ribeiro, C.C.; Barbosa, M.A.; Paul, A.J.; Watts, J.F. (BiomaterialsBIOMATERIALS, 1997)
Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) analyses have been used to investigate the dissolution of hydroxyapatite in the presence of titanium chloride suggesting the substitution of titanium ions for calcium in the hydroxyapatite structure. The surface analytical data suggest that titanium was incorporated within the solid phase as titanium phosphate. Comparison of relative ion intensities in the ToF-SIMS spectra reveals changes in the composition of the surface chemistry of hydroxyapatite. These relative ion intensities show that the maximum surface uptake of titanium occurred at a solution concentration of 500 ppm titanium chloride for a time of incubation of 30 min. These data correlate with that obtained using XPS highlighting the semi-quantitative information which ToF-SIMS can provide.Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS) analyses have been used to investigate the dissolution of hydroxyapatite in the presence of titanium chloride suggesting the substitution of titanium ions for calcium in the hydroxyapatite structure. The surface analytical data suggest that titanium was incorporated within the solid phase as titanium phosphate. Comparison of relative ion intensities in the ToF-SIMS spectra reveals changes in the composition of the surface chemistry of hydroxyapatite. These relative ion intensities show that the maximum surface uptake of titanium occurred at a solution concentration of 500 ppm titanium chloride for a time of incubation of 30 min. These data correlate with that obtained using XPS highlighting the semi-quantitative information which ToF-SIMS can provide.
Cited By (since 1996): 28Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(96)00134-2PubMed ID: 9068892Language of Original Document: EnglishCorrespondence Address: Davies, M.C.; Lab. Biophysics and Surface Analysis, Department Pharmaceutical Sciences, University of Nottingham, Nottingham NG7 2RD, United KingdomChemicals/CAS: Biocompatible Materials; Cations; Ceramics; Durapatite, 1306-06-5; Titanium, 7440-32-6References: Hench, L.L., Wilson, J., Bioceramics (1991) MRS Bull, p. 62. , September;Katz, J.L., Harper, R.A., (1990) Concise Encyclopedia of Medical and Dental Materials, p. 87. , ed. D. F. Williams, Pergamon Press, Oxford; Posner, A.S., Betts, F., Synthetic amorphous calcium phosphate and its relation to bone mineral structure (1975) Acct Chem Res, 8, p. 2373; De Groot, K., (1981) Biocompatibility of Clinical Implant Materials. Vol. I, 1, p. 199. , ed. D. F. Williams, CRC Press, Boca Raton; Van Blitterswijk, C.A., Grote, J.J., Kuijpers, W., Daems, W.T., De Groot, K., Macropore tissue ingrowth: A quantitative and qualitative study on hydroxyapatite ceramic (1986) Biomaterials, 7, p. 137; Jarcho, M., Calcium phosphate ceramics as hard tissue prosthetics (1981) Clin Orthop Rel Res, 157, p. 259; De Groot, K., Geesink, R., Klein, C.P.A.T., Serekian, P., Plasma sprayed coatings of hydroxylapatite (1987) J Biomed Mater Res, 21, p. 1375; Kay, J.F., Golec, T.S., Riley, R.L., Hydroxyapatite coated sub-periosteal dental implants: Design rationale and clinical experience (1987) J Prosthet Dent, 58, p. 339; Geesink, R.G.T., De Groot, K.A., Klein, C.P.A.T., Chemical implant fixation using hydroxylapatite coatings: The development of a human total hip prosthesis for chemical fixation to bone using hydroxylapatite coatings on titanium substrates (1987) Clin Orthop Rel Res, 225, p. 147; Cook, S.D., Thomas, K.A., Kay, J.F., Jarcho, M., Hydroxyapatite coated titanium for orthopaedic implant applications (1988) Clin Orthop Rel Res, 232, p. 225; Van Blitterswijk, C.A., Grote, J.J., Kuijpers, Blok-Van Hoek, C.J.G., Daems, W.T., Bioreactions at the tissue/hydroxyapatite interface (1985) Biomaterials, 6, p. 243; De Lange, G.L.A., Donath, K., Interface between bone tissue and implants of solid hydroxyapatite-coated titanium implants (1989) Biomaterials, 10, p. 121; Craig, G.T., Brook, I.M., Lamb, D.J., Tissue response to subperiosteal implantation of dense hydroxyapatite: Case report (1989) Biomaterials, 10, p. 133; Lemons, J.E., Hydroxyapatite coatings (1988) Clin Orthop Rel Res, 235, p. 220; Van Blitterswijk, C.A., Grote, J.J., (1989) Critical Reviews in Biocompatibility, 5 (ISSUE 1), p. 13. , CRC Press; Driessens, F.C.M., (1983) Bioceramics of Calcium Phosphate, p. 1. , ed. K. de Groot, CRC Press, Boca Raton; Van Raemdonck, W., Ducheyne, P., DeMeester, P., (1984) Metal and Ceramic Biomaterials Vol. II, Strength and Surface, 2, p. 143. , eds P. Ducheyne and G. W. Hastings, CRC Press, Boca Raton; Lee, D.R., (1988) Dissolution Characterisation of Commercially Available Hydroxylapatite Particulate, , MSc thesis, University of Alabama at Birmingham; Whithead, R.Y., Lucas, L.C., Lacefield, W.R., The effect of dissolution on plasma sprayed hydroxylapatite coating on titanium (1993) Clin Materials, 12, p. 31; Driessens, F.C.M., Van Dijk, J.W.E., Borggreven, J.M.P.M., Biological calcium phosphates and their role in the physiology of bone and dental tissues I. Composition and solubility of calcium phosphates (1978) Calcif Tiss Res, 26, p. 127; LeGeros, R.Z., Tung, M.S., Chemical stability of carbonate and fluoride containing apatites (1983) Caries Research, 17, p. 419; Christoffersen, M.R., Thyregood, H.C., Christoffersen, J., Effects of aluminium (III), chromium (II), and iron (III) on the rate of dissolution of calcium hydroxyapatite crystals in the absence and presence of the chelating agent desferrioxamine (1987) J Calcif Tiss Int, 41, p. 27; Blumenthal, N.C., Cosma, V., Inhibition of apatic formation by titanium and vanadium ions (1989) J Biomed Mater Res, 23, p. 13; Ducheyne, P., Van Raemdonck, W., Heughebaert, J.C., Heughebaert, M., Structural analysis of hydroxyapatite coatings on titanium (1986) Biomaterials, 7, p. 97; Ellies, L.G., Nelson, D.G.A., Featherstone, J.D.B., Crystallographic structure and surface morphology of sintered carbonated apatites (1988) J Biomed Mater Res, 22, p. 541; Posner, A.S., The structure of bone apatite surfaces (1985) J Biomed Mater Res, 19, p. 241; Tudor, A.M., Davies, M.C., Melia, C.D., Anderson, D., Hastings, C., Santos, J.D., Barbosa, M., Morrey, S., The analysis of biomedical hydroxyapatite powders and hydroxyapatite coatings on metallic implant by near-IR Fourier transform Raman spectroscopy (1993) Spectrochimica Acta, 5-6, p. 675; Van Raemdonck, W., Ducheyne, P., De Meester, P., Auger electron spectroscopic analysis of hydroxyapatite coatings on titanium (1984) J Am Ceramic Soc, 67, p. 381; Smith, D.C., Murray, D.G., Zuccolin, J.D., Ruse, N.D., Surface characteristics of hydroxyapatite and adhesive bonding. 1. Surface characterisation (1987) J Adhesion, 22, p. 291; Meachim, G., Williams, D.F., (1973) J Biomed Mater Res, 13, p. 555; Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , ed. C. V. Mosby, London; Ribeiro, C.C., (1994), MSc. Thesis, University of PortoEccles, A.J., Vickerman, J.C., (1989) J Vac Sci Technol, A7, p. 234; Briggs, D., Hearn, M.J., Interaction of ion beams with polymer, with particular respect to SIMS (1986) Vacuum, 36, p. 1005; Ribeiro, C.C., Barbosa, M.A., Influence of metal ions on the dissolution behaviour of hydroxyapatite (1991) Bioceramics, 4, p. 145. , eds W. Bonfield, G. H. Hastings and K. E. Tanner, Butterworth-Heinemann; Reed, N.M., Vickerman, J.C., (1993) Surface Characterisation of Advanced Polymers, p. 83. , eds L. Sabbatini and P. G. Zambonin, Weinheim, VCH; Davies, M.C., Lynn, R.A.P., Paul, A.J., Vickerman, J.C., Heller, J., ToF-SIMS and XPS analysis of the surface chemical structure of some linear poly(ortho esters) (1991) Macromolecules, 24, p. 5508; Davies, M.C., Leadley, S.R., Paul, A.J., Vickerman, J.C., Heller, J., Franson, N.M., Probing the surface chemical structure of some novel poly(ortho-esters) prepared with N-methyl and N-phenyl ethanolamine by time-of-flight secondary ion mass spectrometry (ToF-SIMS) (1992) Polymers for Advanced Technologies, 3, pp. 293-301; Briggs, D., Ratner, B.D., A semi-quantitative SIMS analysis of the surfaces of random ethyl methacrylate:-Hydroxyethylmethacrylate copolymer films (1988) Polym Comm, 29, p. 6; Hearn, M.J., Ratner, B.D., Briggs, D., SIMS and XPS studies of poly(urethane) surfaces. I. Preliminary studies (1988) Macromolecules, 21, p. 2950; Briggs, D., Analysis of polymer surfaces by SIMS. VII. Homopolymer and copolymer nylons (1987) Org Mass Spectrom, 22, p. 91
Keywords: article; Bioceramic hydroxyapatite; Biocompatible Materials; biomaterial; Biomaterials; Cations; ceramic prosthesis; ceramics; Composition; Dissolution; Durapatite; hydroxyapatite; information processing; mass spectrometry; Phosphates; priority journal; Radiography; Secondary ion mass spectrometry; Spectrometry, Mass, Secondary Ion; Spectrometry, X-Ray Emission; Spectrophotometry; Substitution reactions; Surface chemistry; surface property; Surface structure; Time of flight secondary ion mass spectrometry; Time-of-flight secondary ion mass spectrometry; Titanium; Titanium chloride; X ray photoelectron spectroscopy; X-ray photoelectron spectroscopy

Iron Determination in Osteoblast-Like Cell Culture Medium by Adsorptive Cathodic Stripping Voltammetry with a Mercury Microelectrode - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Mercury film microelectrodes were used to determine iron in osteoblast-like cell culture medium by performing adsorptive cathodic stripping voltammetry in the presence of catechol. The optimized analytical conditions are a catechol concentration of 5.00×10
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomedica, Depto. de Engenharia Química, Universidade do Porto, Praça Coronel Pacheco, 1, 4050 Porto, PortugalReferences: Cigada, A., (1994) Proc. Symp. Compatibility of Biomedical Implants, 94 (15), pp. 185-192. , (Eds.: P. Kovacs, N.S. Istephanous), The Electrochemical Society, Pennington, NJ;Pohler, O.E.M., (1983) Biomaterials in Reconstrutive Surgery, p. 158. , C.V. Mosby, St. Louis; Black, J., Oppenheimer, P., Morris, D.M., Peduto, A.M., Clark, C.C., (1987) J. Biomed. Mater. Res., 21, p. 1213; Sunderman, F.W., Hopper, S.M., Swift, T., Rezuke, W.N., Ziebra, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Traisnel, M., Maguer, D., Hildebrand, H.F., (1990) Clin. Mater., 5, p. 309; Moore, R.M., Hamburger, S., Jeng, L.J., Hamilton, P.M., (1991) J. Appl. Biomater., 2, p. 127; Henning, E.F., Raithel, H.J., Schaller, K.H., Dohler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Albore-Saavedra, J., Vuitch, F., Delgado, R., Wiley, E., Hagler, H., (1994) Am. Surg. Pathol., 18, p. 83; Buechel, F.F., Drucker, D., Jasty, M., Jiranek, W., Harris, W.H., (1994) Clin. Orthop. Related Res., 298, p. 202; Valenta, P., Rutzel, H., Nurnberg, H.W., Stoeppler, M., (1977) Z. Anal. Chem., 285, p. 25; Nurnberg, H.W., (1977) Electrochim. Acta, 22, p. 935; Nurnberg, H.W., (1978) Proc. Anal. Div. Chem. Soc., 15, p. 275; Golimowski, S.J., Valenta, P., Stoepper, M., Nurnberg, H.W., (1979) Talanta, 26, p. 649; Cox, J.A., Majda, M., (1980) Anal. Chim. Acta, 118, p. 271; Van Den Berg, C.M.G., Huang, Z.Q., (1984) J. Electroanal. Chem., 177, p. 269; Wang, J., Mahmoud, J.S., (1986) J. Electroanal. Chem., 208, p. 383; Van Den Berg, C.M.G., Nimmo, N., Abollino, O., Mentasti, E., (1991) Eleclroanalysis, 3, p. 477; Sousa, J.P., Morais, S., Pereira, M.C., Pereira, M.L., Carvalho, G.S., Barbosa, M.A., (1994) Biomaterials, 15, p. 821; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 56; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., (1993) In Vitro Cell. Dev. Biol., 29 A, p. 699; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., (1994) Clin. Mater., 15, p. 173; Winter, G.D., (1974) J. Biomed. Mater. Res. Symp., 5, p. 11; De Vernejoul, M.C., Pointillart, A., Golenzer, C.C., Morieux, C., Bielakoff, J., Modrowski, D., Miravet, L., (1985) Metals in Bone, pp. 321-331. , (Ed: N.D. Priest), MTT Press Dordrecht; Pend, J., Jin, W., (1992) Anal. Chim. Acta, 264, p. 213; Van Den Berg, C.M.G., (1984) Anal. Chim. Acta, 164, p. 195; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, M., Tolg, G., (1979) Talanta, 26, p. 681; Huizenga, D.L., Rester, D.R., (1984) J. Electroanal. Chem., 164, p. 229; Capodaglio, G., Van Den Berg, C.M.G., Scarponi, G., (1987) J. Electroanal. Chem., 235, p. 275; Torrance, K., Gatford, C., (1986) Analyst, 111, p. 359; Wang, J., Lu, J., Olsen, K., (1992) Analyst, 117, p. 1913; Miller, J.N., (1991) Analyst, 116, p. 3; Morais, S., Sousa, J.P., Fernandes, H., Carvalho, G.S., (1994) Last Minute Posters Abstracts Book, 11th European Conference on Biomaterials, pp. 10-11. , Pisa, Italy; Lugowski, S., Smith, D.C., Van Loon, J.C., (1987) J. Biomed. Mater. Res., 21, p. 657
Keywords: Cell culture medium; Iron; Mercury film microelectrode

Mineralization in serially passaged human alveolar bone cells - Fernandes, M.H.; Costa, M.A.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
Well-characterized human bone cell cultures have been regarded as a useful tool to study bone control mechanisms and also to analyse bone/biomaterials interactions. In the present study, human alveolar bone cells were cultured in a-minimal essential medium (α-MEM) containing 10% foetal bovine serum (FBS), 50 μg/ml ascorbic acid, 10 mM sodium β-glycerophosphate and either in the presence or in the absence of 10 nM dexamethasone (Dexa). Cultures were characterized concerning cell viability/proliferation, alkaline phosphatase (ALP), acid phosphatase (ACP) and tartraric acid resistant phosphatase (TRAP) activities, and formation of mineralized areas. Cell proliferation increased gradually for approximately 20 days. In the presence of Dexa, cells formed isolated or interconnected multilayered clusters that increased with culture time. Histochemical assays revealed strong positive reactions for ALP and calcium and phosphates deposits, mainly in relation to cells associated with the clusters. High levels of ALP activity (biochemical determination) were observed. Cells cultured in the absence of Dexa showed significantly lower ALP activity and no calcium and phosphates deposits were present. Serially passaged cells kept the proliferation rate constant but a decrease in ALP activity was observed either in the presence or in the absence of Dexa. The ability to form mineralized areas (cultures fed with Dexa) also decreased on serial subculture.Well-characterized human bone cell cultures have been regarded as a useful tool to study bone control mechanisms and also to analyse bone/biomaterials interactions. In the present study, human alveolar bone cells were cultured in α-minimal essential medium (α-MEM) containing 10% foetal bovine serum (FBS), 50 μg/ml ascorbic acid, 10 mM sodium β-glycerophosphate and either in the presence or in the absence of 10 nM dexamethasone (Dexa). Cultures were characterized concerning cell viability/proliferation, alkaline phosphatase (ALP), acid phosphatase (ACP) and tartaric acid resistant phosphatase (TRAP) activities, and formation of mineralized areas. Cell proliferation increased gradually for approximately 20 days. In the presence of Dexa, cells formed isolated or interconnected multilayered clusters that increased with culture time. Histochemical assays revealed strong positive reactions for ALP and calcium and phosphates deposits, mainly in relation to cells associated with the clusters. High levels of ALP activity (biochemical determination) were observed. Cells cultured in the absence of Dexa showed significantly lower ALP activity and no calcium and phosphates deposits were present. Serially passaged cells kept the proliferation rate constant but a decrease in ALP activity was observed either in the presence or in the absence of Dexa. The ability to form mineralized areas (cultures fed with Dexa) also decreased on serial subculture.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018598430983Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Rua do Doutor Roberto Frias, 4200 Porto, PortugalReferences: Spector, M., Cease, C., Tong, X., (1989) Crit. Rev. Biocompat., 5, p. 269;Van Blitterswijk, C.A., Bakker, D., Hesseling, S.C., Koerten, H.K., (1991) Biomaterials, 12, p. 187; Galante, J.O., Lemons, J., Spector, M., Wilson Jr., P.D., Wright, T.M., (1991) J. Orthop. Res., 9, p. 760; Bagambisa, F.B., Kappert, H.F., Schilli, W., (1994) J. Oral Maxillofac. Surg., 5, p. 52; Bruijn, J.D., Bovell, Y.D., Blitterwijk, C.A., (1994) Biomaterials, 15, p. 543; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27; Davies, J.E., Chernecky, R., Loweenberg, B., Shiga, A., (1991) Cells and Materials, 1, p. 3; Bruijn, J.D., Davies, J.E., Flach, J.S., De Groot, K., Blitterwijk, C.A., (1992) Mater. Res. Soc. Symp. Proc., 252, p. 63; Puleo, D.A., Bizios, R., (1992) J. Biomed. Mater. Res., 26, p. 291; Bruijn, J.D., Klein, C.P., De Groot, K., Van Blitterswijk, C.A., (1992) J. Biomed. Mater. Res., 26, p. 1365; Bruijn, J.D., Klein, C.P., De Groot, K., Van Blitterswijk, C.A., (1993) Cells and Materials, 3, p. 407; Shen, X., Roberts, E., Peel, S.A., Davies, J.E., (1993) Cells and Materials, 3, p. 257; Meyer, U., Szulczewski, D.H., Moller, K., Heide, H., Jones, D.B., (1993) Cells and Materials, 3, p. 129; Meyer, U., Szulczewski, D.H., Brackhaus, R.H., Atkinson, M., Jones, D.B., (1993) Biomaterials, 14, p. 917; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Gotoh, Y., Hiraiwa, K., Nagayama, M., (1990) Bone and Mineral, 8, p. 23; Berstein, A., Bernauer, I., Marx, R., Geurtsen, W., (1992) Biomaterials, 13, p. 98; Schmiddt, R., Kulbe, K.D., (1993) Bone and Mineral, 20, p. 211; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Benayahu, D., Kletter, Y., Zipori, D., Wientroub, S., (1989) J. Cell Physiol., 140, p. 1; Wong, M.-M., Rao, L.G., Ly, H., Hamilton, L., Tong, J., Sturtridge, W., Mcbroom, R., Murray, T.M., (1990) J. Bone Miner. Res., 5, p. 803; Leboy, P.S., Beresford, J.N., Devlin, C., Owen, M.E., (1991) J. Cell Physiol., 146, p. 370; Shalhoub, V., Conlon, D., Tassinari, M., Quinn, C., Partridge, N., Stein, G.S., Lian, J.B., (1992) J. Cell Biochem., 50, p. 425; Cheng, S.-L., Yang, J.W., Rifas, L., Zhang, S.-F., Avioli, L.V., (1994) Endocrinology, 134, p. 277; Bellows, C.G., Aubin, J.E., Heersche, J.M.N., (1991) Bone and Mineral, 14, p. 27; Satomura, K., Nagayama, M., (1991) Acta Anat., 142, p. 97; Van Straalen, J.P., Sanders, E., Prummel, M.F., Sanders, G.T.B., (1991) Clin. Chem. Acta, 201, p. 27; Aufmkolk, B., Hauschka, P.V., Schwartz, E.R., (1987) Calcif. Tissue Int., 37, p. 228
Keywords: Acid phosphatase; Acid resistance; alkaline phosphatase; alveolar bone; article; ascorbic acid; Bioassay; Biocompatibility; Biomaterials; Bone; bone cell; Bovinae; Cell culture; cell proliferation; Characterization; Chemical reactions; controlled study; culture medium; dexamethasone; Foetal bovine serum; glycerophosphate; Histochemical assays; histochemistry; human; Human alveolar bone cells; human cell; mineralization; Minimal essential medium; Phosphates; priority journal; Proteins; tartaric acid; Tartraric acid resistant phosphatase; Tissue culture

Nickel Determination in Osteoblast-Like Cell Culture Medium by Adsorptive Cathodic Stripping Voltammetry with a Mercury Microelectrode - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
The purpose of this study is to investigate the influence of nickel, which is an alloying element in commonly used metallic biomaterials, on the biomaterials mineralization process. An electrochemical method was developed to quantify this metal ion in osteoblast-like cell culture medium (OST) by performing adsorptive cathodic stripping voltammetry (CSV) with dimethylglyoxime (DMG) at a mercury film microelectrode (MFM). The optimized analytical conditions and the square-wave CSV parameters for the analysis are: DMG concentration: 5.00 × 10
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomedica, Depto. de Engenharia Química, Universidade do Porto, Praça Coronel Pacheco, 1, 4050 Porto, PortugalReferences: Williams, D.F., (1981) Biomaterials and Biocompatibility: An Introduction, in Fundamental Aspects of Biocompatibility, 1. , CRC Press, Boca Raton, FL;Tsalev, D.L., Zaprianov, Z.K., (1983) Atomic Absorption Spectrometry in Occupational and Environmental Health Practice, 1. , CRC Press, Boca Raton, FL; Fishbein, L., Mehlman, M.A., (1987) Advances in Modern Environmental Toxicology, pp. 145-183. , CRC Press, Boca Raton, FL; Costa, M., (1989) Env. Health. Perspect., 81, p. 73; Ward, J., Thornbury, D.D., Lemons, J.., Dunham, W.., (1990) Clin. Orthoped., 252, p. 299; Florence, T.M., (1970) J. Electroanal. Chem., 27, p. 273; Batley, J.E., Florence, T.M., (1976) J. Electroanal. Chem., 72, p. 121; Wang, J., Zadeii, Z., (1988) J. Electroanal. Chem., 246, p. 297; Daniele, S., Baldo, M.A., Ugo, P., Mazzocchin, G., (1989) Anal. Chim. Acta, 219, p. 9; Daniele, S., Baldo, M.A., Ugo, P., Mazzocchin, G., (1989) Anal. Chim. Acta, 219, p. 19; Eskilsson, H., Haraldsson, C., Jagner, D., (1985) Anal. Chim. Acta., 175, p. 79; Economou, A., Fielden, P.R., (1993) Analyst, 118, p. 47; Wightman, R.M., Wipt, D.O., (1989) Voltammetry at Ultramicroelectrodes, pp. 335-336. , Ed: A.J. Bard, Marcel Dekker, New York; Pereira, M.C., Pereira, M.L., Sousa, J.P., (1995) Biomed. Lett., 52, p. 235; Sousa, J.P., Morais, S., Pereira, M.C., Pereira, M.L., Carvalho, G.S., Barbosa, M.A., (1994) Biomaterials, 15, p. 821; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci.: Mater. Med., 6, p. 56; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tiss. Res., 254, p. 317; Morais, S., Sousa, J.P., Fernandes, H., Carvalho, G.S., (1994) Last Minute Posters Abstracts Book, 11th European Conference on Biomaterials, Pisa, Italy, pp. 10-11; Peng, J., Jin, W., (1992) Anal. Chim. Acta, 264, p. 213; Gunawardena, G., Hills, G., Montenegro, I., Scharifker, B., (1982) J. Electroanal. Chem., 138, p. 225; Milchev, A., Scharifker, B., Hills, G., (1981) J. Electroanal. Chem., 132, p. 277; Sousa, J.P., (1991), Ph.D. Dissertation, University of UtahBailey, F., Malinski, T., Kiechle, F., (1991) Anal. Chem., 63, p. 395; Wightman, R.M., (1981) Anal. Chem., 53, pp. 1125A; Turner, A.P.F., Karube, I., Wilson, G.S., (1987) Biosensors Fundamentals and Applications, , Oxford University Press, Oxford; Golas, J., Galus, Z., Osteryoung, J., (1987) Anal. Chem., 59, p. 389; Baranski, A.S., (1987) Anal. Chem., 59, p. 662; Kounaves, S.P., (1992) Anal. Chem., 64, p. 2998; Feinberg, J.S., Bowyer, W.J., (1993) Microchem. J., 47, p. 72; Kounaves, S.P., Deng, W., (1993) Anal. Chem., 65, p. 375; Bustin, D., Mesaros, S., Rievaj, M., Tomcik, P., (1995) Electroanalysis, 4, p. 7; Ostapczuk, P., Valenta, P., Nurnberg, H., (1986) J. Electroanal. Chem., 214, p. 51; Pihlar, B., Valenta, P., Nurnberg, H.W., (1981) Z. Anal. Chem., 307, p. 337; Gammelgaar, B., Andersen, J.R., (1985) Analyst, 110, p. 1197; Vos, L., Komy, Z., Reggers, G., Rockens, E., Van Grieken, R., (1986) Anal. Chim. Acta, 184, p. 271; Torrance, K., Gatford, C., (1985) Talanta, 32, p. 273; Braun, H., Metzgar, M., (1984) Z. Anal. Chem., 318, p. 321; Adeloju, S.B., Bond, A.M., Briggs, M.H., (1984) Anal. Chim. Acta, 164, p. 181; Wahdat, F., Neeb, R., (1985) Z. Anal. Chem., 320, p. 334; Kotz, L., Henze, G., Kaiser, G., Pahlke, S., Veber, R., Tolg, G., (1979) Talanta, 26, p. 681; Wurfels, M., Jackwerth, E., Stoeppler, M., (1989) Anal. Chim. Acta, 226, p. 17; Wurfels, M., Jackwerth, E., Stoeppler, M., (1989) Anal. Chim. Acta, 226, p. 31; Basu, B.J., Rajagopalan, S.R., (1992) Analyst, 117, p. 1623; Bond, A.M., Luscombe, D.L., (1986) J. Electroanal. Chem., 214, p. 21; Van Den Berg, C.M.G., (1991) Anal. Chim. Acta, 250, p. 265; Miller, J.N., (1991) Analyst, 116, p. 3; Wu, T.G., Wong, J.L., (1991) Anal. Chim. Acta, 246, p. 301; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27; Wehmeyer, K.R., Wightman, R.M., (1985) Anal. Chem., 57, p. 1989; Nurnberg, H.W., (1977) Electrochim. Acta, 22, p. 935
Keywords: Cell culture medium; Mercury film microelectrode; Nickel

Nickel Quantification in Mice Organs by Adsorptive Cathodic Stripping Voltammetry Using Mercury Microelectrodes - Pereira, M.C.; Faria, J.L.; Reis, M.L.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1997)
Mercury film microelectrodes (MFMs) were used to quantify trace levels of nickel accumulated in mice organs samples after dosing the mice with a physiological solution containing 150 ppm of Ni ions over a period of time, by performing adsorptive cathodic stripping square wave voltammetry (AdSWV). The residues obtained after digestion of the biological organs with nitric acid which affects the electrochemical response of Ni were investigated by XRD and IR spectrometry and found to be mainly composed by p-nitrobenzoic acid. Electrochemical conditions for the quantification of Niwith MFMs in the biological solutions were optimized. The electrochemical data compared favorably with that obtained by atomic absorption spectrometry.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomedica, Depto. de Engenharia Química, Faculdade Engenharia da Univ. do P., Praça do Coronel Pacheco, 1, P-4050 Porto, PortugalReferences: Mark H.B., Jr., (1964) J. Electroanal. Chem., 7, p. 276;Crow, D.R., Rose, M.E., (1979) Electrochim. Acta, 24, p. 41; Smith, R.G., Windom, H.L., (1980) Anal. Chim. Acta, 113, p. 39; Cantwell, F.F., Nielsen, J.S., Hrudey, E., (1982) Anal. Chem., 54, p. 1498; Pearson, R.M., Siem, H.J., (1977) Anal. Chem., 49, p. 580; Basu, B.J., Rajagopalan, S.R., (1992) Analyst, 117, p. 1623; Wu, T., Wong, J.L., (1990) Anal. Chim. Acta, 235, p. 457; Flora, C., Nieboer, E., (1980) Anal. Chem., 52, p. 1013; Pihlar, B., Valenta, P., Nurnberg, H.W., (1986) J. Electroanal. Chem., 214, p. 157; Martell, A.E., Smith, R.M., (1977) Critical Stability Constants, 3. , Plenum Press, New York; Eriksrud, E., (1975) J. Electroanal. Chem., 60, p. 41; Zhang, H., Wollast, R., Vire, J., Patriache, G.J., (1989) Analyst, 114, p. 1597; Ostapczuk, P., Valenta, P., Nurnberg, H.W., (1986) J. Electroanal. Chem., 214, p. 51; Economou, A., Fielden, P.R., (1993) Analyst, 118, p. 47; Brett, C.M.A., Oliveira Brett, A.M.C.F., Pereira, J.L.C., (1991) Electroanalysis, 3, p. 683; Adeloju, S.B., Bond, A.M., Briggs, M.H., (1984) Anal. Chim. Acta, 164, p. 181; Wang, J., (1985) Stripping Analysis, , VCH, Deerfield Beach, FL; Bond, A.M., Fleischmann, M., Robinson, J., (1984) J. Electroanal. Chem., 172, p. 11; Ewing, A.C., Dayton, M.A., Wightman, R.M., (1981) Anal. Chem., 53, p. 1942; Montenegro, M.I., Queirós, M.A., Dashbach, J.L., (1991) Microelectrodes: Theory and Applications, , NATO-ASI, Kluwer Academic Publishers, Amsterdam, The Netherlands; Scharifker, B., Hills, G.J., (1981) J. Electroanal. Chem., 130, p. 81; Sousa, J.P., (1991), Ph. D. Thesis, University of UtahSousa, J.P., (1994) J. Electroanal. Chem., 372, p. 151; Sousa, J.P., Morais, S.B., Pereira, M.C., Pereira, M.L., Carvalho, G.S., Barbosa, M.A., (1994) Biomaterials, 15, p. 821; Sousa, J.P., Pereira, M.C., (1994) Portug. Electrochem. Acta, 12, p. 63; Wehmeyer, K.R., Wightman, R.M., (1985) Anal. Chem., 57, p. 1989; Kovacs, P., Istephanous, N.S., (1994) Compatibility of Biomedical Implants, , The Electrochemical Society, Pennington, NJ; Pereira, M.C., Sousa, J.P., (1995) Portug. Electrochem. Acta, 13, p. 477; Abreu, A.M., Tracana, R.B., Carvalho, G.S., Sousa, J.P., (1996) Biomed. Lett., 52, p. 133; Morais, S., Carvalho, G.S., Sousa, J.P., (1995) Portug. Electrochim. Acta, 13, p. 483; Griffiths, P.R., De Haseth, J.A., (1986) Fourier Transform Infrared Spectrometry, 83. , Chemical Analysis, (Eds: P.J. Elving, J.D. Winefordner) Wiley, New York; Lin-Vien, D., Colthup, N.B., Fateley, W.G., Grasselli, J.G., (1991) The Handbook of Infrared and Roman Characteristic Frequencies of Organic Molecules, , Academic Press, New York; Pereira, M.L., Pereira, M.C., Sousa, J.P., (1995) Biomed, Lett., 52, p. 235
Keywords: Adsorptive stripping voltammetry; Mice organs; Microelectrodes; Nickel

Preparation and characterization of fluoride-substituted apatites - Jha, L.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
Apatites were prepared with three different fluoride concentrations: 0.0 mM (pure hydroxyapatite) 2.5 mM and 5 mM. Reactions were performed in aqueous medium using a reaction between diammonium orthophosphate and calcium nitrate 4-hydrate and ammonium fluoride at temperatures of 3°, 25°, 60° and 90°C. The effects of reaction temperature and fluoride concentration on the crystal morphology, phase purity and crystallinity of the precipitates were observed, using transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and ion chromatography. Transmission electron micrographs revealed that the crystallites precipitated at 3°C were spheroidal, but became increasingly acicular with increasing precipitation temperature. X-ray diffraction results indicated that all the materials produced were phase pure and that the crystallinity of apatites prepared at higher precipitation temperatures was higher than those prepared at lower precipitation temperatures. A significant difference in the a-axis dimension of fluoride-substituted apatites was observed, as compared to hydroxyapatite. FTIR spectroscopy revealed a hydroxyl band at 3568 cm
Cited By (since 1996): 90Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Jha, L.J.; National Institute of Biomedical Engineering, University of Porto, Rua dos Bragas, 4099 Porto, PortugalReferences: Betts, F., Norman, C., Posner, S.R., (1981) J. Cryst. Growth, 53, p. 63;Arends, I., Tencate, I.M., (1981) J. Cryst. Growth, 53, p. 135; Boivin, G., Meunier, P.J., (1990) The Metabollic and Molecular Basis of Acquired Disease, , edited by R. D. Cohen, B. Lewis, K. G. M. M. Alberti and A. M. Desman Bailliere Tindall, London; Van Den Hock, W.G.M., Fenstra, T.P., DeBruyn, P.L., (1980) J. Phys. Chem., 84, p. 3312; LeGeros, R.Z., Kijkowska, R., Jia, W., LeGeros, J.P., (1988) J. Fluorine Chem., 41, pp. 53-64; Barone, J.P., Nancollas, G.H., (1978) J. Dent. Res., 57, pp. 735-742; Moreno, E.C., Krewask, M., Zahradink, R.T., (1974) Nature, 247, p. 64; Nancollas, G.H., Ahmed, Z., Koutsoukos, P., (1979) ACS Symposium Series, 93, pp. 475-497. , American Chemical Society, Washington, DC; Moreno, E.C., Varughese, K., (1981) J. Cryst. Growth, 53, p. 20; Pantumvanit, P., Feagin, F.F., Koulourides, T., (1977) Caries Res., 11, p. 52; Meyer, I.L., Nancollas, G.H., (1972) J. Dent. Res., 51, p. 1443; Ishikawa, K., Eanes, E.D., Tung, M.S., (1994) J. Dent. Res., 73, p. 1462; Duff, E., (1971) J. Chem. Soc. A, p. 33; Driessens, F.C.M., (1988) Bioceramics of Calcium Phosphate, pp. 1-33. , edited by K. deGroot CRC Press, Boca Raton, FL; Christoffersen, J., Christoffersen, M.R., Johansen, T., (1995) 12th European Conference of Biomaterials, , Porto, Portugal; Christoffersen, J., (1980) J. Cryst. Growth, 49, p. 29; Christoffersen, M.R., Christoffersen, J., Kibalczyc, W., (1990) J. Cryst. Growth, 106, p. 349; Christoffersen, M.R., Christoffersen, J., (1990) J. Cryst. Growth, 121, p. 349; Tenhuisen, K.S., Brown, P.W., (1994) J. Dent. Res., 73, p. 598; Kandori, K., Yasukawa, A., Ishikawa, T., (1995) Chem. Mater., 1, p. 26; Ishikawa, K., Eanes, E.D., Tung, M.S., (1994) J. Dent. Res., 73, p. 1462; Dorozhkin, S.V., (1994) Russian J. Inorg. Chem., 39, p. 217; Larson, A.C., Von Dreele, R.B., Lujan Jr., M., (1990) GSAS-Generalised Crystal Structure Analysis System, , Neutron Scattering Centre, Los Alamos National Laboratory, California; Abrahams, I., Knowles, J.C., (1994) J. Mater. Chem., 4, p. 185
Keywords: Apatites; Chromatographic analysis; Composition effects; crystal structure; Fluorine compounds; Fourier transform infrared spectroscopy; Ion chromatography; Phase composition; Phase purity; Phosphate minerals; Precipitation (chemical); Thermal effects; transmission electron microscopy; X ray diffraction analysis

Processing and in vitro degradation of starch/EVOH thermoplastic blends - Reis, R.L.; Mendes, S.C.; Cunha, A.M.; Bevis, M.J. (Polymer InternationalPolym. Int., 1997)
This paper describes the processing dependence of the mechanical properties of three blends of starch/ethylene vinyl alcohol (EVOH) with potential uses as biomaterials. These blends exhibit a distinct rheological behaviour and mechanical performance. Using shear controlled orientation in injection moulding (Scorim) it was possible to induce anisotropy into the mouldings and to simultaneously enhance stiffness and ductility. Degradation was studied in simulated physiological solutions (Hank's balanced salt solution) with and without added bovine serum. Both the dry weight loss and the changes in mechanical properties were determined for ageing periods up to 80 days. The degradation behaviour proved to be strongly dependent on the formulation of the material studied, and on the addition of proteins. The susceptibility of the starch/EVOH blends to degradation when sterilised with ethylene oxide (EtO) was also studied, and showed that the polymers could stand one EtO sterilisation cycle. However, two consecutive cycles severely degraded the polymer structure and properties.
Cited By (since 1996): 77Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, University of Porto, FEUP, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Hayashi, T., (1994) Prog. Polym. Sci., 19, p. 663;Daniels, A.U., Andriano, K.P., Smutz, W.P., Chang, M.K.O., Heller, J., (1994) J. Appl. Biomater., 5, pp. 5l; Andriano, K.P., Pohjonen, T., Tormalla, P., (1994) J. Appl. Biomater., 5, p. 133; Knowles, J.C., Hastings, G.W., (1992) J. Mater. Sci.: Mater. Med., 3, p. 352; Rokkanen, P.U., (1991) Ann. Med., 23, p. 109; Reis, R.L., Cunha, A.M., (1995) J. Mater, Sci.: Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Advanced Techniques, 1, p. 784; Bastioli, C., Bellotti, V., Del Giudice, L., Lombi, R., (1991) PCT Int. Pat. Appl, , WO91/02025; Bhattarcharya, M., Vaidya, U.R., Zhang, D., Narayan, R., (1995) J. Appl Polym. Sci., 57, p. 539; Bastioli, C., Bellotti, V., Del Guidice, L., Gilli, G., (1993) J. Environ. Polym. Degrad., 1, p. 181; Bastioli, C., Bellotti, V., Rallis, A., (1994) Rheol. Acta., 33, p. 307; Griffin, G.J.L., (1994) Polym. Degrad. Stabil, 45, p. 241; Ogbona, G.L., Kalay, G., Allan, P.S., Bevis, M.J., (1995) J. Appl. Polym. Sci., 58, p. 213; Allan, P.S., Bevis, M.J., (1987), Br. Pat., 2170-140-BAllan, P.S., Bevis, M.J., (1987) Plast. Rubb. Process. Applic., 1, p. 3; Allan, P.S., Bevis, M.J., (1990) Comp. Manuf., 2, p. 79; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) Polymers in Medicine and Surgery, p. 195. , eds J. Courtney et al. Institute of Materials, London; Bastioli, C., Bellotti, V., Camia, M., Del Giudice, L., Rallis, A., (1994) Biodegradable Plastics and Polymers, p. 200. , eds Y. Doi and K. Fukuda. Eisevier, Amsterdam
Keywords: Aging of materials; Anisotropy; Biodegradable polymers; Biodegradation; Biomaterials; Degradation; Ductility; Ethylene oxide; Ethylene vinyl alcohol; Hank's salt solution; Injection molding; Polyethylenes; Polymer blends; Polyvinyl alcohols; Processing; Proteins; rheology; Shear controlled orientation injection molding (Scorim); Starch; Sterilisation; Stiffness

Production, bonding strength and electrochemical behaviour of commercially pure Ti/Al 2O 3 brazed joints - Paiva, O.C.; Barbosa, M.A. (Journal of Materials ScienceJ Mater Sci, 1997)
The brazing of commercially pure titanium to Al 2O 3 has been studied. Two different brazing alloys within the Ag-Cu-Ti system and pure silver were selected as bonding agents. Titanium hydride (TiH 2) additions were also tested, with the aim of improving the wetting of the ceramic surface by the melted brazing alloy. The mechanical and electrochemical behaviour of the produced joints was assessed, and related to chemical and morphological features resulting from an analysis by scanning electron microscopy and energy dispersive spectroscopy. It was possible to produce joints presenting high integrity, good strength and high resistance to corrosion. The best results were obtained when using an Ag-26Cu-3Ti brazing alloy. The addition of TiH 2 increased the mechanical properties, leading to a maximum bonding strength of 80 ± 8 MPa, as determined in three-point bending tests. In most of the cases, for a maximum deflection of 5 mm, there was only a partial detachment of the ceramic/metal joints. The lowest values for the corrosion rates (i corr = 1.38 μA cm
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: JMTSALanguage of Original Document: EnglishCorrespondence Address: Paiva, O.C.; INEB-Inst. de Engenharia Biomedica, Praça do Coronel Pacheco 1, 4050 Porto, PortugalReferences: Paiva, O.C., Barbosa, M.A., (1995) Advances in Materials Science and Implant Orthopaedic Surgery, p. 275. , edited by R. Kossowsky and N. Kossowsky NATO ASI Series, Dordercht, The Netherlands;Hongqi, H., Zhihao, J., Xiaotian, W., (1994) J. Mater. Sci., 29, p. 5041; Santella, M.L., (1992) Ceram. Bull., 6, p. 947; Schwartz, M.M., (1990) Ceramic Joining, , ASM International, Ohio, USA; Nicholas, M., Mortimer, D., (1985) Mater. Sci. Technol., 1, p. 657; Kelkar, G.P., Carim, A.H., (1993) Ceramic Transactions - Structrual Ceramics Joining II, , edited by A. J. Moorhead, R. E. Loehman and S. M. Johnson American Ceramic Society, Ohio, USA; Li, J.-G., (1994) Ceram. Int., 20, p. 391; Mizuhara, H., Huebel, E., Oyama, T., (1989) Ceram. Bull., 9, p. 1591; Jackson, M.D., (1966) Welding Methods and Metallurgy, , Griffin Editions, London; Loehman, R.E., Tomsia, A.P., (1988) Ceram. Bull., 2, p. 375; Barbosa, M.A., Rocha, L., Pures, P., (1993) Monitoring of Orthopedic Implants - A Biomaterials/Microelectronics Challenge, p. 222. , edited by F. Burny and R. Pures Elsevier Science, North-Holland; Cassidy, R., Pence, R., Moddeman, W., (1989) Ceram. Eng. Sci. Proc., 10, p. 1582; Barbier, F., Peytour, C., Revcolevschi, A., (1990) J. Am. Ceram. Soc., 6, p. 1582; Loehman, R.E., Tomsia, A.P., (1992) Acta Metall. Mater., 40, pp. S75; Nicholas, M.G., Mortimore, D.A., (1985) Mater. Sci. Technol., 1, p. 657; Nicholas, M.G., (1986) Br. Ceram. Trans. J., 85, p. 144; Nicholas, M.G., Crispin, R.M., (1989) Ceram. Eng. Sci. Proc., 10, p. 1602; Misra, A.K., (1991) Metall. Trans., 22 A, p. 715; Stern, M., Geary, A.L., (1957) Corrosion, 13, p. 139; Barbosa, M.A., (1992) Biomaterials - Hard Tissue Repair and Replacement, p. 257. , edited by D. Muster Elsevier Science, North-Holland; Uhlig, H.H., (1967) Corrosion and Corrosion Control, , Wiley, New York; Shreir, L.L., (1978) Metal/Environment Reactions, 1. , Newnes-Butterworths, London
Keywords: Agents; Aluminum compounds; Aluminum trioxide; Bond strength (materials); Bonding; Brazed joints; Brazing; Brazing alloys; Corrosion resistance; Energy dispersive spectroscopy; Interfaces (materials); Joints (structural components); Scanning electron microscopy; Silver alloys; Strength of materials; Titanium; Titanium compounds; Titanium hydride

Structure development and control of injection-molded hydroxylapatite-reinforced starch/EVOH composites - Reis, R.L.; Cunha, A.M.; Allan, P.S.; Bevis, M.J. (Advances in Polymer TechnologyAdv Polym Technol, 1997)
This article reports on the development of novel composites of starch-based polymers reinforced with hydroxylapatite (HA). Two different grades of blends of starch and ethylene vinyl alcohol copolymers were reinforced with up to 30% (wt) of sintered and nonsintered HA. The initial compounding stage was carried out either in a rotating drum or by twin-screw extrusion (TSE). Compounds were injection molded using both conventional molding and a shear-controlled orientation in injection molding (Scorim) technique. It was possible to obtain composites with very good mechanical properties, approaching those of cortical bone. The best results were achieved for 30% sintered HA composites processed by TSE and Scorim, due to the in situ formation of HA fibers, and the development of molecular orientation and more compact microstructures in the moldings. This was confirmed by SEM analysis of the fracture surfaces, x-ray diffraction, and Raman spectroscopy. The biodegradability of the composites was also assessed and was found to be faster than that of the matrix. © 1997 John Wiley & Sons, Inc.
Cited By (since 1996): 53Export Date: 21 November 2012Source: ScopusCODEN: APTYDLanguage of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, Faculty of Engineering, University of Porto, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Hayashi, T., (1994) Prog. Polym. Sci., 19, p. 663;Rokkanen, P.U., (1991) Ann. Med., 23, p. 109; Knowles, J.C., Hastings, G.W., (1992) J. Mater. Sci. Mater. Med., 3, p. 352; Adriano, K.P., Pohjonen, T., Tormalla, P., (1994) J. Appl. Biomater., 5, p. 133; Daniels, A.U., Andriano, K.P., Smutz, W.P., Chang, M.K.O., Heller, J., (1994) J. Appl. Biomater., 5, p. 51; Bastioli, C., Bellotti, V., Del Guidice, L., Gilli, G., (1993) J. Environ. Polym. Degrad., 1, p. 181; Griffin, G.J.L., (1994) Polym. Degrad. Stabil., 45, p. 241; Stepto, R.F.T., Tomka, I., (1987) Chimia, 41, p. 76; Bhattarcharya, M., Vaidya, U.R., Zhang, D., Narayan, R., (1995) J. Appl. Polym. Sci., 57, p. 539; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Adv. Technol., 7, p. 784; Wang, M., Bonfield, W., Hench, L.L., (1995) Bioceramics 8, p. 383. , J. Wilson and L. L. Hench (Eds). Butterworth-Heinemann, New York; Verheyen, C.C.P.M., Wijn, J.R., Van Blitterswijk, C.A., De Groot, K., (1992) J. Biomedd. Mater. Res., 26, p. 1277; Verheyen, C.C.P.M., Klein, C.P.A.T., De Blieck-Hogervorst, J.M.A., Wolke, J.G.C., Van Blitterswijk, C.A., De Groot, K., (1993) J. Mater. Sci. Mater. Med., 4, p. 58; Higashi, S., Yamamuro, T., Nakamura, T., Ikada, Y., Hyon, S.H., Jamshidi, K., (1986) Biomaterials, 7, p. 183; Knowles, J.C., Hastings, G.W., (1993) J. Mater. Sci. Mater. Med., 4, p. 102; Oréfice, R.L., La Torre, G.P., West, J.K., Hench, L.L., (1995) Bioceramics 8, p. 409. , J. Wilson, and L. L. Hench (Eds)., Butterworth-Heinemann, New York; Allan, P.S., Bevis, M.J., British Patent 2170-140-B (1987)Allan, P.S., Bevis, M.J., (1987) Plast. Rubber Proc. Appl., 7, p. 3; Allan, P.S., Bevis, M.J., (1990) Comp. Manuf., 2, p. 79; Bastioli, C., Bellotti, V., Rallis, A., (1994) Rheol. Acta, 33, p. 307; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int, 43, p. 347
Keywords: Biodegradation; Composition effects; Compounding (chemical); Copolymers; Extrusion molding; hydroxyapatite; Injection molding; Microstructure; Molecular orientation; Phosphate minerals; Polymer blends; Polyvinyl alcohols; Reinforced plastics; Rotating drum extrusion; Starch; Twin screw extrusion

Treatments to induce the nucleation and growth of apatite-like layers on polymeric surfaces and foams - Reis, R.L.; Cunha, A.M.; Fernandes, M.H.; Correia, R.N. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
In this work, a bioactive glass is used as a percusor of calcium-phosphate (Ca-P) film deposition onto several polymer-based materials. Both bioinert (high molecular weight polyethylene, HMWPE), and biodegradable (corn starch-based blends, SEVA-C) polymers, unreinforced or reinforced with hydroxylapatite (HA), were coated by the very simple proposed route. Also polyurethane (PU) foams, with an open-cell structure, were mineralized by the proposed method. In fact, it was possible to induce the growth of the Ca-P films not only at the surface, but also in the bulk of the PU foam. These cellular materials are intended for cancellous bone replacement applications. The morphology of the formed films was strongly dependent on the used substrate, its polar character, and on the presence of HA in its composition, as observed by SEM. Nevertheless, a well defined needle like structure was observed in all samples at high magnifications. The Ca:P ratios of the films were between 1.5 and 1.7, i.e. in the range of tricalcium phosphate-hydroxylapatite. Raman spectroscopy and thin-film x-ray diffraction (XRD) evidenced the formation of mostly amorphous calcium-phosphate films. After scraping the coating from the polymer surface and heat-treating the resulting powder at 1000°C for 1 h, HA and β-tricalcium phosphate (TCP) typical peaks were found on XRD patterns.In this work, a bioactive glass is used as a percussor of calcium-phosphate (Ca-P) film deposition onto several polymer-based materials. Both bioinert (high molecular weight polyethylene, HMWPE), and biodegradable (corn starch-based blends, SEVA-C) polymers, unreinforced or reinforced with hydroxylapatite (HA), were coated by the very simple proposed route. Also polyurethane (PU) foams, with an open-cell structure, were mineralized by the proposed method. In fact, it was possible to induce the growth of the Ca-P films not only at the surface, but also in the bulk of the PU foam. These cellular materials are intended for cancellous bone replacement applications. The morphology of the formed films was strongly dependent on the used substrate, its polar character, and on the presence of HA in its composition, as observed by SEM. Nevertheless, a well defined needle like structure was observed in all samples at high magnifications. The Ca:P ratios of the films were between 1.5 and 1.7, i.e. in the range of tricalcium phosphate-hydroxylapatite. Raman spectroscopy and thin-film x-ray diffraction (XRD) evidenced the formation of mostly amorphous calcium-phosphate films. After scraping the coating from the polymer surface and heat-treating the resulting powder at 1000 °C for 1 h, HA and β-tricalcium phosphate (TCP) typical peaks were found on XRD patterns.
Cited By (since 1996): 51Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018514107669Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; INEB-Inst. Biomedical Engineering, Praca do Coronel Pacheco 1, 4050 Porto, PortugalTradenames: Hostalen GM9255F, hoechst, Germany; SEVA-CManufacturers: hoechst, GermanyReferences: Lowenstam, H.A., Weiner, S., (1989) On Biomineralization, , Oxford University Press, Oxford;Mann, S., (1988) Nature, 332, p. 119; Mann, S., (1991) Endeavour, 15, p. 120; Mann, S., (1993) Nature, 365, p. 499; Heur, A.H., Fink, D.J., Laraia, V.J., Calvert, P.D., Kendall, K., Messing, G.L., Blackwell, J., Caplan, A.I., (1992) Science, 255, p. 1098; Hench, L.L., (1991) J. Amer. Ceram. Soc., 74, p. 1487; Legeros, R.Z., Orly, I., Gregoire, M., Daculsi, G., (1991) The Bone-Biomaterial Interface, p. 76. , edited by J. E. Davies University of Toronto Press, Torento; Hench, L.L., (1995) Chem. & Indust., 17, p. 547; Hayakawa, S., Isuru, S., Iida, H., Ohtsuki, C., Osaka, A., (1996) Phys. Chem. Glasses, 37, p. 188; Li, P., Ye, X., Kangasniemi, I., De Blieckhogervorst, J.M.A., Klein, C.P.A.T., De Groot, K., (1995) J. Biomed. Matter. Res., 29, p. 325; Li, P., Othsuki, C., Kokubo, T., Nakanish, K., Soga, N., Nakamura, T., Yamamuro, T., (1992) J. Amer. Ceram. Soc., 75, p. 2094; Cho, S.B., Nakanishi, K., Kokubo, T., Saga, N., Ohtsuki, C., Nakamura, T., (1996) J. Biomed. Mater. Res., 33, p. 145; Radder, A.M., Leenders, H., Van Blitterswijk, C.A., (1994) J. Biomed. Mater. Res., 28, p. 141; Ries, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Adv. Technol., 7, p. 784; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1997) Adv. Polym. Technol., , in press; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int., 43, p. 347; Bonfield, W., Grynpas, M.D., Tully, A.E., Bowman, J., Abram, J., (1981) Biomaterials, 2, p. 185; Wang, M., Porter, D., Bonfield, W., (1994) Br. Ceram. Trans., 93, p. 104; Campbell, A.A., Fryxell, G.E., Linehan, J.C., Graff, G.L., (1996) J. Biomed. Mater. Res., 32, p. 111; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1994) J. Amer. Ceram. Soc., 77, p. 2805; Hata, K., Kokubo, T., Nakamura, T., Yamamuro, T., (1995) J. Amer. Ceram. Soc., 78, p. 1049; Kokubo, T., Hata, K., Nakamura, T., Yamamuro, T., (1991) Bioceramics, 4, p. 113. , edited by W. Bonfied, G. W. Hastings and K. E. Tanner Butterworth-Heineman, London; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1995) J. Mat. Sci. Mater. Med., 6, p. 319; Tanahashi, M., Yao, T., Kokubo, T., Minoda, M., Miyamoto, T., Nakamura, T., Yamamuro, T., (1995) J. Biomed. Mater. Res., 29, p. 349; Li, S.H., Liu, Q., Wijn, J.R., Zhou, B.L., De Groot, K., (1997) Biomaterials, 18, p. 389; Li, S.H., Liu, Q., Wijn, J.R., De Groot, K., Zhou, B.L., (1996) J. Mater. Sci. Lett., 15, p. 1882; Golomb, G., Barashi, A., Wagner, D., Nachmias, O., (1993) Clin. Mater., 13, p. 61; Oliveira, J.M., Fernandes, M.H., Correia, R.N., (1992) Bioceramics, 5, p. 7. , edited by T. Yamumuro, T. Kokubu, T. Nakamura and Kobunshi, Konkokai, Tokyo; Oliveira, J.M., Correia, R.N., Fernandes, M.H., (1995) Biomaterials, 16, p. 849
Keywords: Apatite; Bioactivity; Biomaterials; calcium phosphate; cancellous bone; conference paper; Deposition; Film growth; Foamed plastics; glass; Heat treatment; hydroxyapatite; implantation; mineralization; molecular weight; morphology; Nucleation; Phosphate coatings; Phosphate minerals; polyethylene; polymer; polyurethan foam; Polyurethanes; priority journal; Raman spectrometry; Raman spectroscopy; Scanning electron microscopy; X ray diffraction; Zea mays

XPS characterization of surface films formed on surface-modified implant materials after cell culture - Leitão, E.; Barbosa, M.A.; De Groot, K. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1997)
Nitrogen ion-implanted Ti-6AI-4V, Ti-5AI-2.5Fe and 316 L stainless steel and nitrogen or carbon sputter-coated samples were inoculated with rat bone marrow. The interface between the cell layer and the substrata was studied by X-ray photo-electron spectrometry and observed by scanning electron microscopy (SEM). Ca and P were detected on all materials after in vitro cell culture. Titanium appears to be present mainly in the form of TiO 2. Nitrogen ion-implanted Ti-6Al-4V, Ti-5Al-2.5Fe and 316 L stainless steel and nitrogen or carbon sputter-coated samples were inoculated with rat bone marrow. The interface between the cell layer and the substrata was studied by X-ray photo-electron spectrometry and observed by scanning electron microscopy (SEM). Ca and P were detected on all materials after in vitro cell culture. Titanium appears to be present mainly in the form of TiO 2.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018505621839Language of Original Document: EnglishCorrespondence Address: Leitao, E.; INEB-Instituto Engenharia Biomedica, FEUP-Faculdade de Engenharia, Universidade do Porto, Praca Coronel Pacheco 7, 4050 Porto, PortugalReferences: Schmidt, H., Exner, H.E., Rück, D.M., Angert, N., Fink, U., Advances in material science and implant orthopaedic surgery (1995) NATO-ASI Series E: Applied Science, 24, pp. 207-221. , edited by R. Kossowsky and N. Kossowsky;Leitão, E., Sá, C., Silva, R.A., Barbosa, M.A., Ali, H., (1995) Corros. Sci., 37, p. 1861; Howlett, C.R., Zreiqat, H., O'Dell, R., Noorman, J., Evans, P., Dalton, B.A., Mcfarland, C., Steele, J.G., (1994) J. Mater. Sci. Mater. Med., 5, p. 715; Gomi, K., Davies, J.E., (1993) J. Biomedical Mater. Res., 27, p. 429; Gomi, K., De Bruijn, J.D., Ogura, M., Davies, J.D., (1993) Cells and Mater., 3, p. 151; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford Jr., J., Dean, D.D., Boyan, B.D., (1995) J. Biomedical Mater. Res., 29, p. 389; Groessner-Schreiber, B., Tuan, R.S., (1992) J. Cell Sci., 101, p. 209; Davies, J.E., Ottensmeyer, P., Shen, X., Hashimoto, M., Peel, S.A.F., (1991) Proceedings of the Bone-Biomaterial Interface Workshop, p. 214. , December 1990, edited by J. E. Davies Univ. Toronto Press; De Brujin, J.D., Klein, C.P.A.T., De Groot, K., Van Blitterswijk, C.A., (1993) Cells and Mater., 3, p. 407; Orr, R.D., De Bruijn, J.D., Davies, J.D., (1992) Cells and Mater., 2, p. 241; Harmand, M.-F., Naji, A., Gonfrier, P., (1994) Clin. Mater., 15, p. 281; Mániatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Hanawa, T., Ota, M., (1991) Biomaterials, 12, p. 767; Hanawa, T., (1991) Proceedings of the Bone-Biomaterial Interface Workshop, p. 4961. , December 1990, edited by J. E. Davies Univ. Toronto Press; Hanawa, T., Ota, M., (1992) Appl. Surface Sci., 55, p. 269; Lausmaa, J., Kasemo, B., Mattsson, H., (1990) Appl. Surface Sci., 44, p. 133; Kasemo, B., Lausmaa, J., (1991) Proceedings of the Bone-Biomaterial Interface Workshops, p. 19. , December 1990, edited by J. E. Davies Univ Toronto Press; Sutherland, D.S., Forshaw, P.D., Allen, G.C., Brown, I.T., Williams, K.R., (1993) Biomaterials, 14, p. 893; Sundgren, J.-E., Bodö, P., Lundström, I., (1986) J. Colloid Interface Sci., 110, p. 9; Leitao, E., Barbosa, M.A., De Groot, K., (1995) J. Mater. Sci. Mater. Med., 6, p. 849; Leitão, E., Barbosa, M.A., De Groot, K., J. Mater. Sci. Mater. Med., , in press; Puleo, D.A., Huh, W.W., (1995) J. Appl. Biomater., 6, p. 109; Thompson, G.J., (1995) J. Appl. Biomater., 6, p. 249; Ikeo, N., Iijima, Y., Niimura, N., Sigematsu, M., Tazava, T., Matsumoto, S., Kojima, K., Nagasawa, Y., (1991) Handbook of X-ray Photo-electron Spectroscopy, , JHOL; Armstrong, N.R., Quinn, R.K., (1977) Surface Sci., 67, p. 451; Ong, J.L., Prince, C.W., Lucas, L.C., (1995) J. Biomed. Mater. Res., 29, p. 165; Ducheyne, P., (1992) J. Colloid Interface Sci., 150, p. 404; Wagner, C.D., Bickham, D.M., (1989) NIST-XPS Database, , National Institute of Standards and Technology
Keywords: Animal cell culture; Animalia; article; Bone; bone marrow; Calcium; Carbon; Cell culture; implant; Implants (surgical); Interfaces (materials); Ion implantation; nitrogen; phosphorus; priority journal; Scanning electron microscopy; Stainless steel; Surface films; surface property; Surface treatment; Titanium alloys; Titanium dioxide; X ray spectrometry

Amino acid and metal content of Crassostrea gigas shell infested by Polydora sp. in the prismatic layer insoluble matrix and blister membrane - Almeida, M.J.; Moura, G.; MacHado, J.; Coimbra, J.; Vilarinho, L.; Ribeiro, C.; Soares-Da-Silva, P. (Aquatic Living ResourcesAquatic Living Resour., 1996)
The spionid polychaete Polydora sp. can live and reproduce inside the oysters' shell, excavating a U-shaped burrow the central portion of which is filled with detritus and particles of dissolved shell. The oyster responds by secreting an organic layer, confining the worm, and later covering it with calcitostracum. This process creates a characteristic "mud blister". Crassostrea gigas were analysed for the organic matrix amino acid content and 14 metals of the whole shell of normal oysters and severely Polydora infested ones. Amino acid, DOPA and FT-Raman analyses were also performed on isolated membranes from the characteristic mud blister and on prismatic layer insoluble matrix (PLIM) of infested oysters, with the aim of detecting any differences between the two organic matrices. Membranes and PLIM composition differ from whole normal shell organic matrix by having lower aspartate and glycine and higher levels of virtually all hydrophobic amino acids, especially alanine. There are no significant differences between membranes and PLIM in the ratio of charged to non-polar amino acids, respectively 0.54 and 0.59. L-DOPA content is also similar in the two matrices with 0.45 (±0.18) and 0.57 (±0.30) ng.mg
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: ALREELanguage of Original Document: EnglishCorrespondence Address: Almeida, M.J.; Laboratório de Fisiologia Aplicada, Instituto de Ciências Biomédicas Abel Salazar, 4050 Porto, PortugalReferences: Allen, J.A., Manganese deposition on the shell of living molluscs (1960) Nature, 185, pp. 336-337;Beedham, G.E., Repair of the shell in species of Anodonta (1965) Proc. Zool. Soc. London, 145, pp. 107-125; Boggess, R.K., Martin, R.B., Copper chelation by DOPA, epinephrine and other catechols (1975) J. Am. Soc. Chem., 97, pp. 3076-3081; Brown, C.H., (1975) Structural Materials in Animals, , Wiley, New York; Bubel, A., An electron microscope study of periostracum repair in Mytilus edulis (1973) Mar. Biol., 20, pp. 235-244; Carriker, M.R., Swann, C.P., Prezant, R.S., Counts, C.L., Chemical elements in the aragonitic and calcitic microstructural groups of shell of the oyster Crassostrea virginica: A proton probe study (1991) Mar. Biol., 109, pp. 289-297; Catherine, M., Blateau, D., Mazurié, J., Le Bec, C., (1990) Anomalies des Coquilles D'huîtres Creuses Crassostrea Gigas Observées sur le Littoral Français en Mai-juin 1989, Dues au ver Polydora et aux Peintures Antisalissures., pp. 13-14. , Rapp. Int. Dir. Ressources Vivantes, IFREMER Nantes; Degens, E.T., Spencer, D.W., Parker, R.H., Paleobiochemistry of Molluscan shell proteins (1967) Comp. Biochem. Physiol., 79, pp. 553-579; Dorsett, D.A., The behavior of Polydora ciliata (Johnst.). Tube building and burrowing (1961) J. Mar. Biol. Assoc. U.K., 41, pp. 577-590; Felix, C.C., Sealy, R.C., Electron spin resonance characterization of radicals from 3-4-dihydroxyphenylalanine: Semiquinone anions and their metal chelates (1981) J. Am. Chem. Soc., 103, pp. 2831-2835; Galstoff, P.S., The American oyster Crassostrea virginica (Gmelin) (1964) Fish. Bull. U.S., p. 64; Gergely, A., Kiss, T., Coordination chemistry of L-DOPA and related ligands (1979) Met. Ions Biol. Syst., 9, pp. 143-172; Haigler, S., Boring mechanism of Polydora websteri inhabiting Crassostrea virginica (1969) Am. Zool., 9, pp. 821-828; Jones, G.M., Saleuddin, A.S.M., Cellular mechanisms of periostracum formation in Physa spp. (Mollusca: Pulmonata) (1978) Can. J. Zool., 56, pp. 2299-2311; Kawaguchi, T., Watabe, N., The organic matrices of the shell of the American oyster Crassostrea virginica Gmelin (1993) J. Exp. Mar. Biol. Ecol., 170, pp. 11-28; Kawaguti, S., Ikemoto, N., Electron microscopy on the mantle of a bivalve Musculus senhousia, during regeneration of shell (1962) Biol. J. Okayama Univ., 8, pp. 31-42; Krampitz, G., Drolshagen, H., Hotta, S., Simultaneous binding of calcium and bicarbonate by conchiolin of oyster shells (1983) Experiemia, 39, pp. 1104-1105; Laukner, G., Diseases of Mollusca: Bivalvia (1983) Diseases of Marine Animals, Vol. II, Bivalvia to Scaphopoda, 2, pp. 477-978. , Biologische Anstalt Helgoland, O. Kinne ed. Hamburg; Levitt, M., A simplified representation of protein conformation for rapid simulation of protein folding (1976) J. Mol. Biol., 104, pp. 59-108; Linderstrom-Lang, K., Duspiva, F., Studies in enzymatic histochemistry. XVI. the digestion of keratin by larvae of clothes moth (Tineola biselliela Humm.) (1936) C. R. Trav. Lab. Carlsberg, Ser. Chim., 21, pp. 1-82; Lowry, O.H., Rosebrough, N.J., Farr, A.L., Randall, R.J., Protein determination with the Folin phenol reagent (1951) J. Biol. Chem., 193, pp. 265-275; Martius, K.V., Schwarzhans, K.E., Preparation of the Mn (II) complex with 3,4-dihydroxyphenylalanine (DOPA) (1978) Z Naturforsch., 33 B, p. 124; Meenaakshi, V.R., Hare, P.E., Watabe, N., Wilbur, K.M., The chemical composition of the periostracum of the molluscan shell (1969) Comp. Biochem. Physiol., 29, pp. 611-620; Nozaki, Y., Tanford, C., The solubility of amino acids and two glycyl peptides in aqueous ethanol and dioxane solutions (1971) J. Biol. Chem., 246, pp. 2211-2217; Saleuddin, A.S.M., Petit, H.P., The mode of formation and the structure of the periostracum (1983) The Mollusca, 4, pp. 199-234. , K. M. Wilbur ed. Academic Press, New York; Sato-Okoshi, W., Okoshi, K., Microstructure of scallop and oyster shells infested with boring Polydora (1993) Nippon Suisan Gakkaishi, 59, pp. 1243-1247; Segar, D.A., Collins, J.D., Riley, J.P., The distribution of the major and some minor elements in marine animals. Part II (1971) Molluscs. J. Mar. Biol. Assoc. U.K., 51, pp. 131-136; Swinehart, J.H., Smith, K.W., Iron and manganese deposition in the periostraca of several bivalve molluscs (1979) Biol. Bull., 156, pp. 369-381; Travis, D.F., Gonsalves, M., Comparative ultrastructure and organization of the prismatic region of two bivalves and its possible relation to the chemical mechanism of boring (1969) Am. Zool., 9, pp. 635-661; Tsujii, T., An electron microscopic study of the mantle epithelial cells of Anodonta sp. during shell regeneration (1976) The Mechanisms of Mineralization in the Invertebrates and Plants, pp. 339-353. , N. Watabe, K. M. Wilbur eds. Univ. South Carolina Press, Columbia; Vovelle, J., Sclérotisation et minéralisation des structures squellettiques chez les Mollusques (1974) Haliotis, 2, pp. 133-165; Waite, J.H., Evidence for the mode of sclerotization in a molluscan periostracum (1977) Comp. Biochem. Physiol., 58 B, pp. 157-162; Waite, J.H., Quinone-tanned scleroproteins (1983) The Mollusca, 1, pp. 467-504. , K. M. Wilbur ed. Academic Press, New York; Waite, J.H., Andersen, S.O., 3,4-dihydroxyphenyl-alanine in an insoluble shell protein of Mytilus edulis (1978) Biochem. Biophys. Acta, 541, pp. 107-114; Wheeler, A.P., Rusenko, K.W., Swift, D.M., Sikes, C.S., Regulation of in vitro and in vivo CaCO 3 crystallization by fractions of oyster shell organic matrix (1988) Mar. Biol., 98, pp. 71-80; Zottoli, R.A., Carriker, M.R., Burrow morphology, tube formation and microarchitecture of shell dissolution by the spionid polychaete Polydora websteri (1974) Mar. Biol., 27, pp. 307-316
Keywords: Amino acids; Crassostrea gigas; Metals; Polydora sp.; Shell organic matrix

Characterization of apatite layer formation on P 2O 5-CaO, P 2O 5-CaO- Na 2O, and P 2O 5-CaO-Na - Jha, L.J.; Santos, J.D.; Knowles, J.C. (Journal of Biomedical Materials ResearchJ. BIOMED. MATER. RES., 1996)
P 2O 5-based glass hydroxyapatite (HA) composites denoted HA-2 oxide, HA-3 oxide, and HA-4 oxide, were immersed in Hank's balanced salt solution for a period of 1, 2, 3, and 4 weeks at 37°C in nonagitated condition for in vitro evaluation. A surface layer was precipitated on the composites that was analyzed using scanning electron microscopy (SEM), X-ray photoelecton spectroscopy, and thin film X-ray diffractometry (TF-XRD). SEM micrographs showed complete coverage of the composite surface by crystallites after immersion of 1 week in the solution, which grew thicker with respect to immersion time. The binding energies measured by XPS indicated apatite formation and the presence of carbonate on the composite surface, showing the newly formed layer was a carbonated apatite. Confirmation of the formed apatite layer was obtained by TF-XRD. 2O 5-based glass hydroxyapatite (HA) composites denoted HA-2 oxide, HA-3 oxide, and HA-4 oxide, were immersed in Hank's balanced salt solution for a period of 1, 2, 3, and 4 weeks at 37°C in nonagitated condition for in vitro evaluation. A surface layer was precipitated on the composites that was analyzed using scanning electron microscopy (SEM), X-ray photoelectron spectroscopy, and thin film X-ray diffractometry (TF-XRD). SEM micrographs showed complete coverage of the composite surface by crystallites after immersion of 1 week in the solution, which grew thicker with respect to immersion time. The binding energies measured by XPS indicated apatite formation and the presence of carbonate on the composite surface, showing the newly formed layer was a carbonated apatite. Confirmation of the formed apatite layer was obtained by TF-XRD.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/(SICI)1097-4636(199608)31:4<481::AID-JBM7>3.0.CO;2-HPubMed ID: 8836844Language of Original Document: EnglishCorrespondence Address: Jha, L.J.; IRC in Biomedical Materials, Queen Mary and Westfield College, Mile End Road, London E1 4NS, United KingdomChemicals/CAS: HydroxyapatitesReferences: Hyakuna, K., Yamamuro, T., Kotoura, Y., Oka, M., Kokubo, T., Kushitani, H., Surface reactions of calcium phosphate ceramics to various solutions (1990) J. Biomed. Mater. Res., 24, pp. 471-488;Ebisawa, Y., Kokubo, T., Ohura, K., Yamamuro, T., Bioactivity of CaO·SiO 2-based glasses: In vitro evaluation (1990) J. Mater. Sci.: Mater. Med., 1, pp. 239-244; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Yamamuro, T., Chemical reaction of bioactive glass and glass ceramics with a simulated body fluid (1992) J. Mater. Sci.: Mater. Med., 3, pp. 79-83; Li, P., Yang, Q., Zhang, F., Kokubo, T., The effect of residual glassy phase in a bioactive glass-ceramic on the formation of its surface apatite layer in vitro (1992) J. Mater. Sci.: Mater. Med., 3, pp. 452-456; Ohtsuki, C., Aoki, Y., Kokubo, T., Yamamuro, T., Nakamura, T., Characterization of apatite layer formed on bioactive glass-ceramic A-W (1992) Bioceramics, 5, pp. 87-94. , T. Yamamuro, T. Kokubo, and T. Nakamura (eds.), Kokunshi Kankokai, Japan; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Effects of ions dissolved from bioactive glass-ceramic on surface apatite formation (1993) J. Mater. Sci.: Mater. Med., 4, pp. 1-4; Kohri, M., Miki, K., Waite, D., Nakajima, H., Okabe, T., In vitro stability of biphasic calcium phosphate ceramics (1993) Biomaterials, 14, pp. 299-304; Andersson, O.H., Kangasniemi, I., Calcium phosphate formation at the surface of bioactive glass in vitro (1991) J. Biomed. Mater. Res., 25, pp. 1019-1030; Kokubo, T., Kushitani, H., Sakka, S., Kitsugi, T., Yamamuro, T., Solutions able to reproduce in vivo surface-structure changes in bioactive glass-ceramic A-W (1990) J. Biomed. Mater. Res., 24, pp. 721-734; Santos, J.D., Knowles, J.C., Hastings, G.W., Bonfield, W., "Sintered hydroxyapatite compositions and method for the preparation thereof," British Patent No. 9,213,774.4 (1993)Santos, J.D., Reis, R.L., Knowles, J.C., Hastings, G.W., Monteiro, F.J., Microstructural characterisation of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Santos, J.D., Knowles, J.C., Monteiro, F.J., Hastings, G.W., Development of a glass reinforced hydroxyapatite with enhanced mechanical properties: Physical properties and in vitro studies (1992) Bioceramics, 5, pp. 35-41. , T. Yamamuro, T. Kokubo, and T. Nakamura (eds.), Kokunshi Kankokai, Japan; Knowles, J.C., Abrahams, I., Bonfield, W., Effect of reinforcing glass composition on phase transformation and crystallographic parameters in hydroxyapatite (1993) Bioceramics, 6, pp. 191-196. , P. Ducheyne and D. Christiansen (eds.), Butterworth Heinemann, New York; Knowles, J.C., Bonfield, W., Development of a glass reinforced hydroxyapatite with enhanced mechanical properties. The effect of glass composition on mechanical properties and its relationship to phase changes (1993) J. Biomed. Mater. Res., 27, pp. 1591-1598; Burnie, J., Gilchrist, T., Controlled release glass (C.R.C.) - A new biomaterial (1983) Ceramics in Surgery, pp. 169-176. , P. Vincenzini (ed.), Elsevier, Amsterdam; Santos, J.D., Jha, L.J., Monteiro, F.J., Study of surface modifications by x-ray photoelectron spectroscopy on glass reinforced hydroxyapatite composites in a simulated physiological solution (1995) Biomaterials, 16, pp. 521-526; Rehman, I., Hench, L.L., Bonfield, W., Comparison of hydroxycarbonate apatite layers on bioactive glasses with human bone (1993) Bioceramics, 6, pp. 123-128. , P. Ducheyne and D. Christiansen (eds.), Butterworth Heinemann, New York; Landis, W.J., Martin, J.R., X-ray photoelectron spectroscopy applied to gold-decorated mineral standards of biological interest (1984) J. Vac. Sci. Technol., A2, p. 1108; Swift, P., Adventitious carbon - The panacea for energy referencing? (1982) Surface Interface Anal., 4, pp. 47-51; Clark, D.T., Thomas, H.R., Applications of ESCA to polymer chemistry. XVII. Systematic investigation of the core levels of single homopolymers (1978) J. Polym. Sci., Polym. Chem. Ed., 16, pp. 791-820; Verhoeven, J.A., Van Doveren, H., An XPS investigation of the interface of methane, ethyne, ethene, and ethane with barium surface (1982) Surface Sci., 123, pp. 369-383
Keywords: Apatite; article; binding affinity; Biomaterials; bone strength; Calcium Compounds; Carbonates; Ceramic materials; Characterization; chemical composition; Composite materials; Crystallites; electron microscopy; glass; Glass hydroxyapatite composites; Hank balanced salt solution; hydroxyapatite; Hydroxyapatites; immersion; Microscopy, Electron, Scanning; Molecular Structure; Oxides; prosthesis material; Scanning electron microscopy; scanning tunneling microscopy; Spectrum Analysis; Thin film X ray diffractometry; Thin films; X ray diffraction; X ray diffraction analysis; X ray photoelectron spectroscopy; X-Ray Diffraction

Crystallinity and structural changes in HA plasma-sprayed coatings induced by cyclic loading in physiological media - Reis, R.L.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
In this study hydroxyapatite plasma-sprayed Ti-6A1-4V was characterized by X-ray diffraction (XRD) after being cyclically loaded, while immersed in two different testing environments: Hank's balanced salt solution (HBSS) and an isotonic saline solution (0.15m NaCl). An original method was developed to test these systems under cyclic bending, while immersed in the testing solution. The crystallinity of the coating was calculated, before and after testing. Crystallinity changes were related to coating dissolution rates, measured by atomic absorption spectroscopy (AAS) and by a photocolourimetric method using ascorbic acid. Structural changes induced either by the plasma-spraying procedure or due to corrosion-fatigue tests, namely a preferential dissolution of the coating's amorphous phase, were also found in X-ray diffraction patterns. Long-term immersion tests, without any applied load, were carried out for assessing cyclic loading effects. An immersion for 2 years in static conditions was found to be equivalent to a cyclic test of 27.8 h in the same solution, as measured by the changes on the coating structure and by the amount of coating material lost to the solution.In this study hydroxyapatite plasma-sprayed Ti-6Al-4V was characterized by X-ray diffraction (XRD) after being cyclically loaded, while immersed in two different testing environments: Hank's balanced salt solution (HBSS) and an isotonic saline solution (0.15M NaCl). An original method was developed to test these systems under cyclic bending, while immersed in the testing solution. The crystallinity of the coating was calculated, before and after testing. Crystallinity changes were related to coating dissolution rates, measured by atomic absorption spectroscopy (AAS) and by a photocolourimetric method using ascorbic acid. Structural changes induced either by the plasma-spraying procedure or due to corrosion-fatigue tests, namely a preferential dissolution of the coating's amorphous phase, were also found in X-ray diffraction patterns. Long-term immersion tests, without any applied load, were carried out for assessing cyclic loading effects. An immersion for 2 years in static conditions was found to be equivalent to a cyclic test of 27.8 h in the same solution, as measured by the changes on the coating structure and by the amount of coating material lost to the solution.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00122009Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, FEUP, Univ. of Porto, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Ji, H., Marquis, P.M., (1993) Biomaterials, 14, p. 64;Pfaff, H.G., Willmann, G., Henne, R., (1993) Proceedings of the 10th European Conference on Biomaterials, p. 110. , Davos, Switzerland, 1993, edited by B. Rahn (European Society for Biomaterials); Brown, S.D., (1984) Thin Solid Films, 119, p. 127; Geesink, R.G.T., (1988), PhD thesis, Univ. Leiden, The NetherlandsVan Blitterswijk, C.A., Grote, J.J., Kuypers, W., Blok-Van Hoek, C.J.G., Daems, W.Th., (1985) Biomaterials, 6, p. 243; Ribeiro, C.C., Barbosa, M.A., (1991) Bioceramics 4, p. 145. , edited by W. Bonfield, G. W. Hastings and K. Tanner (Butterworth-Heinemann London); Ducheyne, P., Healy, K.E., (1988) J. Biomed. Mater. Res., 22, p. 1137; Whitehead, R.Y., Lucas, L.C., Lacefield, W.R., (1993) Clin. Mater., 12, p. 31; De Bruijn, J.D., Davies, J.E., Flach, J.S., De Groot, K., Van Blitterswijk, C.A., (1992) Proceedings of the 4th World Congress on Biomaterials - Workshop on Biomaterials and Tissue Interactions, p. 23. , edited by U. Gross (Berlin); Morita, M., Sasada, T., Hayashi, H., Tsukamoto, Y., (1988) J. Biomed. Mater. Res., 22, p. 529; Brown, S.A., Farsnworth, L.J., Merritt, K., Crowe, T.D., (1988) J. Biomed. Mater. Res., 22, p. 321; Kummer, F., Jaffe, W., (1992) J. Appl. Biomater., 3, p. 211; Reis, R.L., Monteiro, F.J., Garrido, A., (1992) Bioceramics 5, p. 25. , Kyoto, November, 1992, edited by T. Yamamura, T. Kokubo and T. Nakamura (Kobunshi Kankokai, Tokyo); Reis, R.L., Monteiro, F.J., (1993) Bioceramics 6, p. 413. , Philadelphia, USA, 1993, edited by P. Ducheyne and D. Christiansen (Butterworth-Heinemann. New York); Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) J. Mater. Sci. Mater. Med., 5, p. 457; Reis, R.L., Monteiro, F.J., (1995) Proceedings of the NATO/ASI on Materials Science and Implant Orthopaedic Surgery II, p. 163. , Chania, Greesce, June 1994. edited by R. Kossowsky and N. Kossowsky (May, NATO/ASI series E: Applied Sciences, Kluwer Press, Amsterdam); Ji, H., Ponton, C.B., Marquis, P.M., (1992) J. Mater. Sci. Mater. Med., 3, p. 283; Weng, J., Liu, X., Zhang, X., Ma, Z., Ji, X., Zyman, Z., (1993) Biomaterials, 14, p. 578; De Groot, K., Klein, C.A.P.T., Wolke, J.G.C., Blieck-Hogervorst, J.M.A., (1990) Handbook of Bio-active Ceramics, 2, p. 133. , edited by T. Yamamuro, L. L. Hench and J. Wilson (CRC Press, Boca Raton, FL); Delécrin, J., Szumuckler-Moncler, S., Daculsi, G., Rieu, J., Duquet, B., (1991) Bioceramics 4, p. 311. , London, September, 1991, edited by W. Bonfield, G. W. Hastings and K. E. Tanner (Butterworth-Heinemann, London); De Bruijn, J.D., Flach, J.S., Leenders, H., Van der Brink, J., Van Blitterswijk, C., (1992) Bioceramics 5, p. 259. , Kyoto, November, 1992, edited by T. Yamamura, T. Kokubo and T. Nakamura (Kobunshi Kankokai, Tokyo)
Keywords: Absorption spectroscopy; article; ascorbic acid; atomic absorption spectrometry; Atomic absorption spectroscopy; balanced salt solution; Bending (deformation); Calculations; Characterization; Corrosion fatigue tests; crystal structure; Crystallinity; Cyclic bending; Dissolution; Fatigue testing; Hanks balanced salt solution; hydroxyapatite; Hydroxyapatite plasma sprayed coatings; immersion; implant; Isotonic saline solution; loading test; Long term immersion tests; materials testing; Modification; Photocolourimetric method; photometry; Plasma spraying; priority journal; sodium chloride; Sprayed coatings; Titanium alloys; Titanium aluminum vanadium alloys; X ray crystallography; X ray diffraction

Effect of hydroxyapatite thickness on metal ion release from Ti6Al4V substrates - Sousa, S.R.; Barbosa, M.A. (BiomaterialsBIOMATERIALS, 1996)
The electrochemical dissolution behaviour of Ti6Al4V alloy coated with hydroxyapatite (HA) by plasma spraying was studied in Hank's balanced salt solution (HBSS) and compared with that of polished and grit-blasted passivated surfaces. Two different nominal thicknesses of HA (50 and 200 μm) were used. Taking a polished passivated surface as reference, grit blasting of the substrate increased the electrical charge used in the oxidation of Ti6Al4V alloy at constant potential, as a result of increased surface area. However, only HA coatings with a thickness of 200 μm were capable of reducing the charge to values lower than those measured for polished surfaces. Electrochemical impedance spectroscopy has also shown that only 200 μm thick coatings are effective in reducing the oxidation rate of the substrate. Furthermore, in potentiostatic experiments the 50 μm thick coating detached from the substrate, which did not occur with the 200 μm thick coating. However, after 6 months immersion in HBSS, detachment occurred in some regions of both coatings. No titanium, aluminium or vanadium were detected in solution by electrothermal atomic absorption spectroscopy. These data indicate that HA is an effective barrier to metal ion release, even for the thinner coatings, due to formation of metal phosphates or to incorporation of metal ions in the HA structure.The electrochemical dissolution behaviour of Ti6Al4V alloy coated with hydroxyapatite (HA) by plasma spraying was studied in Hank's balanced salt solution (HBSS) and compared with that of polished and grit-blasted passivated surfaces. Two different nominal thicknesses of HA (50 and 200 μm) were used. Taking a polished passivated surface as reference, grit blasting of the substrate increased the electrical charge used in the oxidation of Ti6Al4V alloy at constant potential, as a result of increased surface area. However, only HA coatings with a thickness of 200 μm were capable of reducing the charge to values lower than those measured for polished surfaces. Electrochemical impedance spectroscopy has also shown that only 200 μm thick coatings are effective in reducing the oxidation rate of the substrate. Furthermore, in potentiostatic experiments the 50 μm thick coating detached from the substrate, which did not occur with the 200 μm thick coating. However, after 6 months immersion in HBSS, detachment occurred in some regions of both coatings. No titanium, aluminium or vanadium were detected in solution by electrothermal atomic absorption spectroscopy. These data indicate that HA is an effective barrier to metal ion release, even for the thinner coatings, due to formation of metal phosphates or to incorporation of metal ions in the HA structure.
Cited By (since 1996): 62Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/0142-9612(96)89655-4PubMed ID: 8938233Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Praca do Coronel Pacheco 1, 4050 Porto, PortugalChemicals/CAS: Alloys; Biocompatible Materials; Durapatite, 1306-06-5; titanium alloy (TiAl6V4), 12743-70-3; Titanium, 7440-32-6References: Barbosa, M.A., Electrochemical impedance studies on calcium phosphate-metal interfaces (1991) Bioceramics, 4, pp. 325-333. , Bonfield W, Hastings GW, Tanner KE, eds. London: Butterworth-Heinemann;Sousa, S.R., Barbosa, M.A., Electrochemistry of AISI 316L stainless steel in calcium phosphate and protein solutions (1991) J Mater Sci: Mater Med, 2, pp. 19-26; Sousa, S.R., Barbosa, M.A., Corrosion resistance of titanium cp in saline physiological solutions with calcium phosphate and proteins (1993) Clin Mater, 14, pp. 287-294; Li, P., De Groot, K., Calcium phosphate formation within sol-gel prepared titania in vitro and in vivo (1993) J Biomed Mater Res, 27, pp. 1495-1500; Li, P., Kangasniemi, I., De Groot, K., Bonelike hydroxyapatitc induction by a gel-derived titania and a titanium substrate (1994) J Am Ceram Soc, 77, pp. 1307-1312; Ducheyne, P., Healy, K.E., The effect of plasma-sprayed calcium phosphate ceramic coatings on the metal ion release from porous titanium and cobalt-chromium alloys (1988) J Biomed Mater Res, 22, pp. 1137-1163; Weng, J., Liu, X., Zhang, X., Li, X., Thermal decomposition of hydroxyapatite structure induced by titanium and its dioxide (1994) J Mater Sci Lett, 13, pp. 159-161; Castro Ribeiro, C., Barbosa, M.A., Influence of metal ions on the dissolution behaviour of hydroxyapatite (1991) Bioceramics, 4, pp. 145-153. , Bonfield W, Hastings GW, Tanner KE, eds. Butterworth-Heinemann; ASTM G61-86, standard test method for: Conducting cyclic potentiodynamic polarization measurements for localized corrosion susceptibility of iron, nickel, or cobalt based alloys (1989) Annual Book of ASTM Standards, pp. 345-361. , 03.02. Philadelphia, PA: American Society for Testing and Materials; ASTM G 31-72 e1, standard practice for: Laboratory immersion corrosion testing of metals (1989) Annual Book of ASTM Standards, pp. 176-186. , 03.02. Philadelphia, PA: American Society for Testing and Materials; Barbosa, M.A., Surface layers and the reactivity of metallic implants (1992) Biomaterials - Hard Tissue Repair and Replacement, pp. 257-283. , Muster D et al. ed. Amsterdam: Elsevier Science Publishers BV; Rivero, D.P., Fox, J., Skipor, A.K., Urban, R.M., Galante, J.O., Calcium phosphate-coated porous titanium implants for enhanced skeletal fixation (1988) J Biomed Mater Res, 22, pp. 191-201; Oonishi, H., Yamamoto, M., Ishimaru, H., The effect of hydroxyapatite coating on bone growth into porous titanium alloy implants (1989) J Bone Joint Surg, 71 B, pp. 213-216; Bourne, R.B., Rorabeck, C.H., Burkar, B., Kirk, P.G., Ingrowth surfaces - Plasma spray coating to titanium alloy hip replacements (1994) Clin Orthop Rel Res, 298, pp. 37-46; Oonishi, H., Noda, T., Ito, S., Effect of hydroxyapatite coatings on bone growth into porous titanium alloy implants under loaded conditions (1994) J Appl Biomater, 5, pp. 23-37; Moroni, A., Caja, V.L., Egger, E.L., Trinchese, L., Chao, E.Y.S., Histomorphometry of hydroxyapatite coated and uncoated porous titanium bone implants (1994) Biomaterials, 15, pp. 926-930; Bloebaum, R.D., DuPont, J.A., Osteolysis from a press-fit hydroxyapatite-coated implant (1993) J Arthroplasty, 8, pp. 195-202; Bloebaum, R.D., Beeks, D., Dorr, L.D., Savory, C.G., DuPont, J.A., Hofmann, A.A., Complications with hydroxyapatite particulate separation in total hip arthroplasty (1994) Clin Orthop, 298, pp. 19-26; Klein, C.P.A.T., Patka, P., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., Long-term in vivo study of plasma-sprayed coatings on titanium alloys of tetracalcium phosphate, hydroxyapatite and α-tricalcium phosphate (1994) Biomaterials, 15, pp. 146-160; Reis, R.L., Monteiro, F.J., Hastings, G.W., Stability of hydroxyapatite plasma-sprayed coated Ti-6Al-4V under cyclic bending in simulated physiological solutions (1994) J Mater Sci: Mater Med, 5, pp. 457-462; Wang, B.C., Lee, T.M., Chang, E., Yang, C.Y., The shear strength and the failure mode of plasma-sprayed hydroxyapatite coating to bone: The effect of coating thickness (1993) J Biomed Mater Res, 27, pp. 1315-1327; Tranquilli Leali, P., Merolli, A., Palmacci, O., Gabbi, C., Cacchiolo, A., Gonizzi, G., Evaluation of different preparations of plasma-spray hydroxyapatite coating on titanium alloy and duplex stainless steel in the rabbit (1994) J Mater Sci: Mater Med, 5, pp. 345-349
Keywords: Absorption spectroscopy; Alloys; Aluminum; article; Atomic spectroscopy; balanced salt solution; Bioactive coatings; Biocompatible Materials; Biomaterials; Calcium Compounds; Dissolution; Durapatite; Electric charge; Electrochemical dissolution; Electrochemical impedance spectroscopy; electrochemistry; Electrothermal atomic absorption spectroscopy; Hank balanced salt solution; hydroxyapatite; Ion release; Ions; metal ion; Metal ion release; Metal phosphates; Microscopy, Electron, Scanning; Oxidation; Plasma spraying; potentiometry; priority journal; Spectrophotometry, Atomic; Spectroscopy; Substrates; thickness; Thickness effect; Time Factors; Titanium; Titanium alloys; vanadium

Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures - Tomás, H.; Carvalho, G.S.; Fernandes, M.H.; Freire, A.P.; Abrantes, L.M. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15ppm of Co and 8ppm of Cr as analysed by atomic absorption spectroscopy. Stock salt solutions of CoCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products. The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15 ppm of Co and 8 ppm of Cr as analyzed by atomic absorption spectroscopy. Stock salt solutions of COCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Tomas, H.; Faculdade de Ciencias, Universidade de Lisboa, Campo Grande, C1, Piso 5, 1700 Lisboa, PortugalReferences: Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , C. V. Mosby, St. Louis;Black, J., Oppenheiner, P., Morris, R.O.M., Peduto, A.M., Clark, C.C., (1987) J. Biomed. Mater. Res., 21, p. 1213; Sunderman Jr., F.W., Hopfer, S.M., Swift, T., Rezuke, W.N., Ziebka, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Traisnel, M., Maguer, D., Hildebrand, H.F., (1990) Clin. Mater., 5, p. 309; Moore Jr., R.M., Hamburger, S., Jeng, L.J., Hamilton, P.M., (1991) J. Appl. Biomater., 2, p. 127; Henning, E.F., Raithel, H.J., Schaller, K.H., Dòhler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Albore-Saavedra, J., Vuitch, F., Delgado, R., Wiley, E., Hagler, H., (1994) Amer. Surg. Pathol., 18, p. 83; Buechel, F.F., Drucker, D., Jasty, M., Jiranek, W., Harris, W., (1994) Clin. Orthop. Related Res., 298, p. 202; De Bruijn, J.D., (1993), p. 9. , PhD thesis, LeidenNasser, S., Campbell, P.A., Kilgus, D., Kossovsky, N., Amstutz, H.C., (1990) Clin. Orthop., 261, p. 171; Revell, P.A., Weightman, B., Freeman, M.A.R., Roberts, B.V., (1978) Arch. Orthop. Trauma Surg., 91, p. 167; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., (1993) In Vitro Cell. Dev. Biol., 29 A, p. 699; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., (1994) Clin. Mater., 15, p. 173; Tomás, H., Freire, A.P., Abrantes, L.M., (1994) J. Mater. Sci. Mater. Med., 5, p. 446; Lowry, O.H., Rosebrough, N.J., Farr, A.L., Randall, R.J., (1951) J. Biol. Chem., 193, p. 256; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Berridge, M.V., Tan, A.S., (1993) Arch. Biochem. Biophys., 303, p. 474; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., (1993) Biomaterials, 14, p. 359; Martin, A., Clynes, M., (1993) Cytotechnology, 11, p. 49; Carvalho, G.S., Castanheira, M., Diogo, I., Abreu, A.M., Sousa, J.P., Loon, J.A., Van Blitterswijk, C.A., J. Mater. Sci. Mater. Med., , in press; Gotoh, Y., Hiraiwa, K., Nagayama, M., (1990) Bone and Mineral, 8, p. 239; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27
Keywords: Absorption spectroscopy; article; Atomic spectroscopy; Biocompatibility; Bone; Cell culture; Chromium alloys; Cobalt alloys; Corrosion; Corrosion resistance; Cytocompatibility; Enzyme inhibition; human; human cell; Human osteoblasts; Implants (surgical); Orthopaedic alloys; ossification; osteoblast; priority journal; surface property

Fracture toughness of hydroxyapatite reinforced with P 2O 5-CaO glasses containing Na 2O, K 2O and MgO - Silva, P.L.; Santos, J.D.; Knowles, J.C.; Silva, R.F.; Monteiro, F.J. (Transactions of the Annual Meeting of the Society for Biomaterials in conjunction with the International Biomaterials SymposiumTrans Annu Meet Soc Biomater Int Biomater Symp, 1996)
Calcium phosphate materials are widely used in biomedical applications but their poor strength and brittleness limit their use in load bearing applications. To improve their mechanical properties, hydroxyapatite (HA) ceramics were reinforced with P 2O 5-CaO based glasses with additions of Na 2+, Mg 2+ and K + oxides. A composite chemical composition that approaches the inorganic part of bone chemical composition was obtained using HA with calcium phosphate-based glasses. Fracture toughness was significantly enhanced by glass additions, and the decrease in fracture toughness at 1300 and 1350 °C was attributed to grain growth since it significantly increased with sintering temperature.
Conference code: 45651Export Date: 21 November 2012Source: ScopusCODEN: TAMSELanguage of Original Document: EnglishCorrespondence Address: Silva, P.L.; INEB, Porto, Portugal
Keywords: Biomaterials; Bone; Composition effects; Fracture toughness; glass; Grain growth; hardness; Hydroxyapatites; Lime; Magnesia; Phosphate minerals; Potassium compounds; Sodium compounds; Thermal effects

Granules of osteoapatite and glass-reinforced hydroxyapatite implanted in rabbit tibiae - Afonso, A.; Santos, J.D.; Vasconcelos, M.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Granules of a modified hydroxyapatite, glass-reinforced hydroxyapatite composite and commercial hydroxyapatite were implanted in rabbit tibiae. Histological studies were carried out after 1 and 2 months implantation periods using light and fluorescence microscopy. A much higher percentage of bone contact was developed for both the glass-reinforced hydroxyapatite composite and the modified hydroxyapatite when compared to commercial hydroxyapatite (89-91% versus 66%) after 2 months implantation. The mechanism of bone formation and growth around implants is discussed in terms of the influence of elements incorporated into these novel materials which are commonly found in bone tissues, such as Na, K and Mg, and the presence of a soluble β-tricalcium phosphate phase in the microstructure of the composite.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Afonso, A.; Faculty of Dental Medicine, University of Porto, Rua Dr Roberto Frias, 4200 Porto, PortugalChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; magnesium, 7439-95-4; potassium, 7440-09-7; sodium, 7440-23-5References: Ravaglioli, A., Krajewski, A., (1992) Bioceramics-materials, Properties and Applications, p. 100. , Chapman & Hall, London;Cranin, A.N., Ronen, E., Puntoff, R.S.H., Tobim, G., Dibeling, J.B., (1988) J. Biomed. Mater. Res., 22, p. 1165; De Groot, K., Klein, C.P.A.T., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 3. , edited by T. Yamamuro CRC Press, Boston; Hollinger, J.O., Schmitz, J.P., Mizgala, J.W., Hassler, C., (1989) J. Biomed. Mater. Res., 23, p. 17; Cavalheiro, J., Branco, R., Vasconcelos, M., (1991) Proceedings of the 4th International Conference on Bioceramics, p. 205. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner, London, UK Butterworth-Heinemann, Oxford; Santos, J.D., Reis, R.L., Knowles, J.C., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Nery, E.B., Legeros, R.Z., Lynch, K.L., Kalbleisch, J., (1988) J. Dent. Res., 67, p. 178; Ellinger, R.F., Nery, E.B., Lynch, K.L., (1986) Int. J. Period. Restor. Dent., 3, p. 223; Legeros, R.Z., Daculsi, G., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 17. , edited by T. Yamamuro CRC Press, Boston
Keywords: animal experiment; animal tissue; article; Bone; Bone formation; bone growth; Calcium Compounds; calcium phosphate; Composite materials; Fiber reinforced materials; glass; Glass fibers; Glass reinforced hydroxyapatite; Granular materials; histology; hydroxyapatite; implant; Implants (surgical); Magnesium; Microstructure; Modified hydroxyapatite; nonhuman; Optical microscopy; ossification; Osteoapatite; Oxides; Phosphates; Physiological models; potassium; priority journal; rabbit; Rabbit tibiae; Sodium; tibia; X ray diffraction analysis

Histological evaluation of two bioactive cements - Vasconcelos, M.; Afonso, A.; Branco, R.; Planell, J.; Driessens, F.; Cavalheiro, J. (Transactions of the Annual Meeting of the Society for Biomaterials in conjunction with the International Biomaterials SymposiumTrans Annu Meet Soc Biomater Int Biomater Symp, 1996)
Two bioactive bone cements were compared with poly(methylmethacrylate) (PMMA) cement. Cement A was prepared from precipitated hydroxyapatite and tricalcium phosphate, using an aqueous solution of Na 2HPO 4. Cement B was prepared by crushing a bioactive glass composed of SiO 2, CaO, P 2O 5 and Na 2O. The powder was mixed with NH 4H 2PO 4/(NH 4) 2 PO 4 aqueous solution buffered at pH = 7.4. The bioactive cements exhibited different in vivo behaviors but both performed better than PMMA cement.
Conference code: 45651Export Date: 21 November 2012Source: ScopusCODEN: TAMSELanguage of Original Document: EnglishCorrespondence Address: Vasconcelos, M.; INEB-Inst Eng. Biomedica, Porto, Portugal
Keywords: Bioactive bone cements; bone cement; glass; hydroxyapatite; Ion exchange; Lime; pH; Phosphate minerals; Polymethyl methacrylates; Silica; Sodium compounds; Solutions; Sorption; Tricalcium phosphate

Implant recovery and tissue reaction in growing pigs following implantation of packaging materials for injectable electronic identification and monitoring devices - Janssens, S.; Rocha, L.A.; Bosschaerts, L.; Barbosa, M.A.; Puers, R.; Villé, H.; Geers, R. (Preventive Veterinary MedicinePrev. Vet. Med., 1996)
Different materials were used as cylindrical housings (40 mm × 5 mm) for implantable electronic identification and monitoring tags in livestock. A total of 299 pigs received an implant in the right ear base. Wound healing was complete after 6 weeks in all animals, whereas tissue reaction at the site of the transponder started from the first week with highest levels between 6 and 9 weeks. About 10% of pigs showed visible swelling of the tissue surrounding the implant. Severeness of tissue reaction ante-mortem influenced the recovery rate of implants. Histological sections obtained from the pigs at slaughter show signs of an inflammatory response in most of the pigs which was associated with the implantation duration/body weight effect. Overall recovery of implants was 90%. The unfavourable inflammation and recovery results might be attributed to a sub-optimal injection procedure.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: PVMEELanguage of Original Document: EnglishCorrespondence Address: Janssens, S.; Lab. for Agric. Buildings Research, K.U. Leuven, K. Mercierlaan 92, B-3001 Heverlee, BelgiumReferences: Agresti, A., (1990) Categorical Data Analysis, , John Wiley, New York, 558 pp;Report from the working group on transponders (1990) CBSG News, 1 (3), p. 13; Davis, S.D., Gibbons, D.F., Martin, R.L., Levitt, S.R., Smith, J., Harrington, R.V., Biocompatibility of ceramic implants in soft tissue (1972) J. Biomed. Mater. Res., 6, pp. 425-449; Dorn, H.J., Vorstellung des EURO I.D. Systems zur kennzeichnung von tieren mit mikrochips in transpondern (1987) Tierarztl. Umschau, 12, pp. 978-981; Fallon, R.J., Rogers, P.A.M., Use and recovery of implantable electronic transponders in beef cattle (1991) Automatic Electronic Identification Systems for Farm Animals, pp. 61-67. , E. Lambooij (Editor), Commission European Community, Luxembourg; Konermann, H., Identification of horses by implantation of microchips (1991) Automatic Electronic Identification Systems for Farm Animals, pp. 37-43. , E. Lambooij (Editor), Commission European Community, Luxembourg; Lambooij, E., Injectable electronic identification systems: Some veterinary aspects (1991) Automatic Electronic Identification Systems for Farm Animals, pp. 21-27. , E. Lambooij (Editor), Commission European Community, Luxembourg; Lambooij, E., Merks, J.W.M., De techniek en plaats van injectie van elektronische levensnummers in varkens (1989) IVO-Rapp., B-335. , IVO-DLO, Zeist, The Netherlands, 12 pp; Lambooij, E., De Groot, P.H.S., Molenbeek, R.F., Gruys, E., Subcutaneous tissue reaction to polyethylene terephtalate-covered electronic identification transponders in pigs (1992) Vet. Q., 14 (4), pp. 145-147; Interim report following six month checks (1991) Livestock Identification Trial, , MLC, Milton Keynes, UK, 14 pp; Petersen, B., Kunneken, J., Norpoth, A., BIPS: An information and preventive system for pig breeding farms (1989) Pigs News Inf., 10 (4), pp. 473-476; Rao, G.N., Edmondson, J., Tissue reaction to an implantable identification device in mice (1990) Toxicol. Pathol., 18 (3), pp. 412-416; (1989) SAS/STAT User's Guide, Version 6, 4th Edn., 1. , SAS Institute Inc., Cary, NC, 943 pp; Williams, D.F., The response of the body environment to implants (1973) Implants in Surgery, pp. 203-297. , D.F. Williams (Editor), Saunders, London; Williams, D.F., Titanium and titanium alloys (1981) Biocompatibility of Clinical Implant Materials, 1, pp. 188-200. , D.F. Williams (Editor), CRC Press, Boca Raton, FL
Keywords: implant; Implant recovery; Pig; tissue reaction

In vitro calcium phosphate formation on SiO 2-Na 2O-CaO-P 2O 5 glass reinforced hydroxyapatite composite: A study by XPS analysis - Santos, J.D.; Jha, L.J.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
In-vitro apatite layer formation on the surface of a newly developed glass reinforced hydroxyapatite composite was characterized using X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray analysis (EDXA). After 1 week soaking in an acellular simulated body fluid the composite surface was entirely covered by a Ca, P-layer, suggesting a bioactive behaviour. XPS binding energy results revealed that this surface layer was a carbonated and non- stoichiometric apatite with Ca/P ratio of 1.3. This apatite layer was composed of very fine needle-like crystallites. Comparative studies on a commercially available hydroxyapatite showed that a similar apatite layer was also formed on its surface.In-vitro apatite layer formation on the surface of a newly developed glass reinforced hydroxyapatite composite was characterized using X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray analysis (EDXA). After 1 week soaking in an acellular simulated body fluid the composite surface was entirely covered by a Ca, P-layer, suggesting a bioactive behaviour. XPS binding energy results revealed that this surface layer was a carbonated and non-stoichiometric apatite with Ca/P ratio of 1.3. This apatite layer was composed of very fine needle-like crystallites. Comparative studies on a commercially available hydroxyapatite showed that a similar apatite layer was also formed on its surface.
Cited By (since 1996): 42Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; FEUP, Rua dos Bragas, 4099-Porto Codex, PortugalChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8References: Ducheyne, P., (1987) J. Biomed. Mater. Res.: Appl. Biomater., 21 (A2), p. 219;Hench, L.L., (1989) J. Biomed. Mater. Res., 23, p. 685; Hench, L.L., (1991) J. Amer. Ceram. Soc., 7, p. 1487; Jarcho, M., (1988) Bioceramics 1, p. 57. , edited by H. Oonishi, H. Aoki and K. Sawai Ishiyaku Euro America, Tokyo; De Groot, K., (1980) Biomaterials, 1, p. 47; Blitterswijk, C.A.V., Koerten, H.K., Grote, J.J., (1986) Biological and Biomechanical Performance of Biomaterials, p. 27. , edited by P. Cristel, A. Meunier and A. J. C. Lee Elsevier Science Publishers, Amsterdam; Ono, K., Yamamuro, T., Nakamura, T., Kokubo, T., Kotoura, Y., (1988) J. Biomed. Mater. Res., 22, p. 869; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, , Japanese Association of Apatite Science (JAAS), Takayama Press System Centre Co., Inc; Manabe, A., Shigematsu, M., Kobayashi, S., (1987) High Tech Ceramics, p. 63. , edited by P. Vincenzini Elsevier Science Publishers, Amsterdam; Kitsugi, T., Yamamuro, T., Nakamura, T., Kokubo, T., Ono, M., (1987) J. Biomed. Mater. Res., 21, p. 1109; Kokubo, T., Ito, S., Shigematsu, M., Sakka, S., Yamamuro, T., (1985) J. Mater. Sci. Mater. Med., 20, p. 2001; Mestral, F., Drew, R.L.A., (1989) J. Eur. Ceram. Soc., 5, p. 47; Burnie, J., Gilchrist, T., Kobayashi, S., (1983) Ceramics in Surgery, p. 169. , edited by P. Vincenzini Elsevier Science Publishers, Amsterdam; Andersson, O.H., Liu, G., Karlsson, K.H., Niemi, L., Juhanoja, J., (1990) J. Mater. Sci. Mater. Med., 1, p. 219; Knowles, J.C., Rehman, I., Bonfield, W., (1994) Bioceramics 7, p. 85. , edited by O. H. Andersson, R. P. Happonen and A. Yli-Urpo Butterworth Heinemann, Turku, Finland; Santos, J.D., Reis, R.L., Knowles, J.C., Hastings, G.W., Monteiro, F.J., (1994) Biomaterials, 15, p. 5; Santos, J.D., Knowles, J.C., Monteiro, F.J., Hastings, G.W., (1992) Bioceramics 5, p. 35. , edited by T. Yamamuro, T. Kokubo and T. Nakamura Kokunshi Kankokai, Kyoto; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1985) J. Mater. Sci. Mater. Med., 6, p. 448; Wilson, J., Low, S., (1992) J. Appl. Biomater., 3, p. 123; Oonishi, H., Kushitani, S., Yasukawa, E., Hench, L.L., Wilson, J., Tsuji, E., Sugihara, T., (1994) Bioceramics 7, p. 139. , edited by O. H. Andersson, R.-P. Happonen and A. Yli-Urpo, Butterworth Heinemann, Turku, Finland; Neo, M., Nakamura, T., Yamamuro, T., Ohtsuki, C., Kokubo, T., Bando, Y., (1992) J. Biomed. Mater. Res., 26, p. 1419; Hyakuna, K., Yamamuro, T., Kotoura, Y., Kokubo, T., Kushitani, H., (1990) J. Biomed. Mater. Res., 24, p. 471; Kokubo, T., Kushitani, H., Sakka, S., Kitsugi, T., Yamamuro, T., (1990) J. Biomed. Mater. Res., 24, p. 721; Santos, J.D., Jha, L.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Li, P., Ohtsuki, C., Kokubo, T., Nakanishi, K., Soga, N., Nakamura, T., Yamamuro, T., (1993) J. Appl. Biomater., 4, p. 221; Neo, M., Kotani, S., Fujita, Y., Yamamuro, T., Bando, Y., Ohtsuki, C., Kokubo, T., (1992) J. Biomed. Mater. Res., 26, p. 255; Li, P., Yang, Q., Zhang, F., Kokubo, T., (1992) J. Mater. Sci. Mater. Med., 3, p. 452; Kokubo, T., Kushitani, H., Kitsugi, T., Yamamuro, T., (1988) Bioceramics 1, p. 157. , edited by T. Yamamuro, T. Kokubo and T. Nakamura Kokunshi Kankokai, Kyoto; Landis, W.J., Martin, J.R., (1984) J. Vac. Sci. Technol., A2, p. 1108; Andersson, O.H., Kangasniemi, I., (1991) J. Biomed. Mater. Res., 25, p. 1019; Verhoeven, J.A.T., Van Doveren, H., (1982) Surf. Sci., 123, p. 369; Rehman, I., Hench, L.L., Bonfield, W., (1994) Bioceramics 7, p. 123. , edited by O. H. Andersson, R. P. Happonen and A. Yli-Urpo Butterworth Heinemann, Turku, Finland; Turner, N.H., Murday, J.S., Ramaker, D.E., (1980) Anal. Chem., 52, p. 84
Keywords: article; Binding energy; Biocompatibility; Biodegradation; biomaterial; Calcium; calcium phosphate; Characterization; Composite materials; Composition; Energy dispersive x ray analysis; glass; Glass reinforced hydroxyapetite composite; hydroxyapatite; implant; In vitro calcium phosphate formation; Ionic concentration; molecular interaction; Nucleation; Phosphates; phosphorus; priority journal; Scanning electron microscopy; Surfaces; X ray analysis; X ray photoelectron spectroscopy

Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts - Carvalho, G.S.; Castanheira, M.; Diogo, I.; Abreu, A.M.; Sousa, J.P.; Loon, J.A.; Van Blitterswijk, C.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Fibroblasts from normal human skin were cultured for a period of 21 days in the absence or in the presence of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium and nickel ions used either separately (Fe, Cr, or Ni solutions) or combined (Fe+Cr+Ni solution). At several periods of time (4, 7, 14 and 21 days) the cell cultures were analysed for the following parameters: (a) metal ion accumulation by atomic absorption spectrometry; (b) cell morphology and viability by the neutral red assay; (c) cell proliferation by DNA assessment, and enzyme activity by both (d) MTT reduction and (e) acid phosphatase activity. Results showed that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, had opposite effects on fibroblast cultures. In fact, SS-corrosion products caused no apparent effects on cell morphology nor on cell proliferation whereas Fe+Cr+Ni solution stimulated both neutral red uptake and cell proliferation. The enzymatic assays showed that SS-corrosion products caused inhibition of both MTT reduction and acid phosphatase activity in contrast to Fe+Cr+Ni solution which stimulated their activity. Furthermore, in all biological parameters studied, a strong association was observed between the effects of Fe+Cr+Ni solution and Cr alone, suggesting that Cr was the metal ion mostly involved in the stimulatory effects of the combined solution.Fibroblasts from normal human skin were cultured for 21 days in the absence, or presence, of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium, and nickel ions used either separately or combined. At different periods of time, the cell cultures were analyzed for the following parameters: metal ion accumulation by atomic absorption spectrometry; cell morphology and viability by the neutral red assay; cell proliferation by DNA assessment; and enzyme activity by both MTT reduction and acid phosphatase activity. Results show that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, have opposite effects on fibroblast cultures.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; INEB-Instituto Engenharia Biomedica, Portugal Universidade do Minho, Praca Coronel Pacheco, 1, 4000 Porto, PortugalChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; acid phosphatase, 9001-77-8, 9025-88-1; chromium, 16065-83-1, 7440-47-3; DNA, 9007-49-2; iron, 14093-02-8, 53858-86-9, 7439-89-6; neutral red, 553-24-2; nickel, 7440-02-0; stainless steel, 12597-68-1References: Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , C.V. Mosby, St. Louis;Galante, J.O., Lemons, J., Spector, M., Wilson Jr., P.D., Wright, T.M., (1991) J. Orthop. Res., 9, p. 760; Henning, E.F., Raithel, H.J., Schaller, K.H., Döhler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Maloney, W.J., Smith, R.L., Castro, F., Schurman, J., (1993) J. Bone Joint Surg., 75 A, p. 835; Jorgensen, T.J., Munno, F., Mitchell, T.G., Hungerford, D., (1983) Clin. Orthop., 176, p. 124; Jones, L.C., Hungerford, D.S., (1987) Trans Orthop. Res. Soc., 32, p. 317; Stulberg, B.N., Watson, J.T., Shull, S.L., Merritt, K., Crowe, T.D., Stulberg, S.D., Guidry, C.H., (1987) Trans Orthop. Res. Soc., 33, p. 314; Sunderman Jr., F.W., Hopfer, S.M., Swift, T., Rezuke, W.N., Ziebka, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Merritt, K., Brown, S.A., Sharkey, N.A., (1984) J. Biomed. Mater. Res., 18, p. 991; Brown, S.A., Farnsworth, L.J., Merritt, K., Crowe, T.D., (1988) Biomed. Mater. Res., 22, p. 321; Merritt, K., Crowe, T.D., Brown, S.A., (1989) J. Biomed. Mater. Res., 23, p. 845; Merritt, K., Margevicius, R.W., Brown, S.A., (1992) J. Biomed. Mater. Res., 26, p. 1503; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., (1994) Cytobios, 77, p. 73; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 56; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., (1992) Advances in Biomaterials, p. 7. , edited by P. J. Doherty et al. Elsevier, Amsterdam; Vrouwenvelder, W.C.A., Groot, C.G., DeGroot, K., (1993) J. Biomed. Mater. Res., 27, p. 465; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., (1993) Biomaterials, 14, p. 359; Martin, A., Clynes, M., (1991) In Vitro Cell. Dev. Biol., 27 A, p. 183; Borenfreund, E., Puerner, J.A., (1983) J. Tissue Culture Methods, 9, p. 7; Hansen, M.B., Nielsen, S.E., Berg, K., (1989) J. Immunol. Methods, 119, p. 203; Rosdy, M., Grisoni, B., Claus, L.C., (1991) Biomaterials, 12, p. 511; Van Sliedregt, A., Radder, A.M., De Groot, K., Van Blitterswijk, C.A., (1992) J. Mater. Sci. Mater. Med., 3, p. 365; Caughman, W.F., Caughman, G.B., Shiflett, R.A., Rueggeberg, F., Schuster, G.S., (1991) Biomaterials, 12, p. 737; Carvalho, G.S., Bravo, I., (1993) J. Mater. Sci. Mater. Med., 4, p. 366; Harmand, M.F., Bordenave, L., Bareille, R., Naji, A., Jeandot, R., Rouais, F., Ducassou, D., (1991) J. Biomater. Sci. Polymer Edn., 2, p. 67; Katz, A., Feldman, M., Eisenbach, L., (1992) J. Immunol. Methods, 149, p. 117; Naji, A., Harmand, M.F., (1990) J. Biomed. Mater. Res., 24, p. 861; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Berridge, M.V., Tan, S., (1993) Arch. Biochem. Biophys., 303, p. 474
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorption spectroscopy; Acid phosphatase; article; atomic absorption spectrometry; Atomic spectroscopy; Bioassay; Cell culture; Cell morphology; cell proliferation; cell structure; cell viability; Chromium; controlled study; Corrosion; Corrosion products; cytology; DNA; Enzymatic assays; Enzyme Activation; enzyme activity; Enzyme inhibition; fibroblast; human; human cell; Ions; Iron; metal; Metal ion accumulation; Metal salts; Metals; neutral red; Nickel; priority journal; Salts; Skin; skin fibroblast; Stainless steel; Steel corrosion

Mechanical behavior of injection-molded starch-based polymers - Reis, R.L.; Cunha, A.M.; Allan, P.S.; Bevis, M.J. (Polymers for Advanced TechnologiesPolym. Adv. Technol., 1996)
This work evaluates the mechanical performance of injection-molded starch-based copolymers, 60/40 (mol/ mol) starch/poly(ethylene vinyl alcohol), and the possibility of improving material properties through deliberately induced anisotropy during processing. Different types of samples were produced by conventional and shear-controlled injection molding (Scorim) and tested under tensile and impact loading. The behavior of three distinct grades is discussed in terms of the respective fracture morphology (evaluated by scanning electron microscopy). A comparison is made between the behavior of conventional and Scorim samples. The results show that the mechanical properties of the materials used were significantly improved by the employment of the Scorim process. The stiffness values of the conventional moldings were doubled, without reducing the ductility of the polymer. The impact data showed a material sensitivity, and consequent loss of properties, to the localized shear imposed to the melt during processing. This situation is attributed to very narrow mold gates (in the case of pingated systems) and leads to much reduced impact performance.
Cited By (since 1996): 58Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, FEUP, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Rokkanen, P.U., (1991) Ann. Med., 23, p. 109;Danniels, A.U., Adriano, K.P., Smutz, W.P., Chang, M.K.O., Heller, J., (1994) J. Appl. Biomater., 5, p. 51; Baumgart, F.W., Perren, S.M., (1994) Clinical and Laboratory Performance of Bone Plates, p. 42. , J. P. Harvey and R. F. Games, eds., ASTM STP1217, Philadelphia; Knowles, J.C., Hastings, G.W., (1992) J. Mater. Sci.: Mater. Med., 3, p. 352; Knowles, J.C., Hastings, G.W., (1993) J. Mater. Sci.: Mater. Med., 4, p. 102; Bastioli, C., Bellotti, V., Del Guidice, L., Gilli, G., (1993) J. Environ. Polym. Degr., 1, p. 181; Yoshida, Y., Uemura, T., (1994) Biodegradable Plastics and Polymers, p. 443. , Y. Doi and K. Fukuda, eds, Elsevier Science, Tokyo; Bastioli, C., Bellotti, V., Camia, M., Del Giudice, L., Rallis, A., (1994) Biodegradable Plastics and Polymers, p. 200. , Y. Doi and K. Fukuda, eds, Elsevier Science, Tokyo; Allan, P.S., Bevis, M.J., British Patent 2170-140-BAllan, P.S., Bevis, M.J., (1987) Plast. Rubb. Proc. Appl., 7, p. 3; Allan, P.S., Bevis, M.J., (1990) Comp. Manufac., 2, p. 79; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci.: Mater. Med., 6, p. 786; Bastioli, C., Belloti, V., Rallis, A., (1994) Rheological Acta, 33, p. 307
Keywords: Anisotropy; Biomaterials; Copolymers; differential scanning calorimetry; Ductility; fracture; Impact performance; Impact testing; Injection molding; Mechanical performance; Melting temperature; morphology; Narrow mold gates; performance; Scanning electron microscopy; Scorim; Scorim process; Starch-based polymers; Starched based polymers; Stiffness; Tensile testing

Potentiometric Determination of Total and Ionized Calcium in Osteoblast-Like Cell Culture Medium - Morais, S.; Carvalho, G.S.; Sousa, J.P. (ElectroanalysisElectroanalysis, 1996)
The effect of the ionic strength and composition of solutions in the direct potentiometric determination of total and ionized calcium content using a calcium selective electrode was investigated. In the presence of a constant complexation buffer (CCB), the addition of sodium chloride and sodium bicarbonate causes a decrease in the limit of detection of the potentiometric response. When the procedure was tested in osteoblast-like cell culture medium no electrode interferences or method interferences were observed by the presence of proteins, i.e., the total and ionized calcium in this medium can be measured by potentiometric means.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: ELANELanguage of Original Document: EnglishCorrespondence Address: Sousa, J.P.; Inst. de Engenharia Biomédica, Faculdade de Engenharia, Universidade do Porto, Praça Coronel Pacheco, 1, P-4050 Porto, PortugalReferences: Nernst, W., (1886) Z. Phys. Chem., 2, p. 613;Nernst, W., (1889) Z. Phys. Chem., 4, p. 129; Morf, W.E., (1981) The Principle of Ion-Selective Electrodes and of Membrane Transport, , Elsevier, Amsterdam; Hulanicki, A., Trojanowicz, M., (1974) Anal. Chim. Acta, 68, p. 155; Anker, P., Wieland, E., Ammann, D., Dohner, R.E., Asper, R., Simon, W., (1981) Anal. Chem., 53, p. 1970; Manzoni, A., Premoli, P., (1985) Methodology and Clinical Applications of Ion-Selective Electrodes, pp. 131-136. , (Eds: A. H. J. Maas, A. B. T. J. Boink, N. E. L. Saris, R. Sprokholt, P. D. Wimberley), Radiometer, Copenhagen; Hulanicki, A., Lewandowski, R., Michalska, A., Lewenstam, A., (1990) Anal. Chim. Acta, 233, p. 269; Morais, S., Sousa, J.P., Fernandes, H., Carvalho, G.S., (1994) 11th European Conference on Biomaterials, Pisa, pp. 10-11. , Last Minute Posters Abstracts Book, European Society for Biomaterials; Ruzicka, J., Tjell, J.C., (1969) Anal. Chim. Acta, 47, p. 475; Ross, J.W., (1967) Science, 15, p. 1378; Rechnitz, G.A., Hseu, T.M., (1969) Anal. Chem., 41, p. 111; Oreskez, I., Hirsch, C., Douglas, K.S., Kupfer, S., (1968) Clin. Chim. Acta, 21, p. 203; Recomendations for Nomenclature of Ion-Selective Electrodes (1994) Pure Appl. Chem., 66, p. 2527; Ringbom, A., (1963) Complexation in Analytical Chemistry, , Interscience, New York; Russell Instruction Manual of Calcium Electrode Model 93-3209; Baudet, S., (1994) Methods in Cell Biology, pp. 93-113. , Academic Press, New York; Scharff, O., (1979) Anal. Chim. Acta, 109, p. 291
Keywords: Cell culture medium; potentiometry; Total and ionized calcium

Reinforcement of hydroxyapatite by adding P 2O 5-CaO glasses with Na 2O, K 2O and MgO - Santos, J.D.; Silva, P.L.; Knowles, J.C.; Talal, S.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Commercial hydroxyapatite was reinforced by adding small amounts (2 and 4 wt%) of P 2O 5-based glasses during its sintering process. The composites prepared had a chemical composition closely related to the mineral part of bone tissues in terms of trace elements usually detected, such as Na, K and Mg. X-ray diffraction analysis (XRD) showed that the glass reinforced-HA composites were composed of a HA matrix and variable amounts of tricalcium phosphate phase, depending on sintering temperature and glass composition. These composites were shown to have much higher biaxial bending strength than sintered HA, 107 MPa for Ha/2% of 35P 2O 5-35CAO-10Na 2O-10K 2O-10MgO glass composite and 28 MPa for sintered HA. The presence of β-tricalcium phosphate in the microstructure of the composites is an important factor in the reinforcement process. Commercial hydroxyapatite was reinforced by adding small amounts (2 and 4 wt%) of P 2O 5-based glasses during its sintering process. The composites prepared had a chemical composition closely related to the mineral part of bone tissues in terms of trace elements usually detected, such as Na, K and Mg. X-ray diffraction analysis (XRD) showed that the glass reinforced-HA composites were composed of a HA matrix and variable amounts of tricalcium phosphate phase, depending on sintering temperature and glass composition. These composites were shown to have much higher biaxial bending strength than sintered HA, 107 MPa for Ha/2% of 35P 2O 5-35CaO-10Na 2O-10K 2O-10MgO glass composite and 28 MPa for sintered HA. The presence of β-tricalcium phosphate in the microstructure of the composites is an important factor in the reinforcement process.
Cited By (since 1996): 49Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Dept. of Metallurgical Engineering, FEUP, University of Porto, Rua dos Bragas, 4099 Porto Codex, PortugalChemicals/CAS: hydroxyapatite, 1306-06-5, 51198-94-8; magnesium oxide, 1309-48-4, 1317-74-4References: Barney, V.C., Levin, M.P., Adams, D.F., (1986) J. Perio Dont., 57, p. 764;Legeros, R.Z., (1988) Adv. Dent. Res., 2, p. 164; Aoki, H., (1991) Science and Medical Applications of Hydroxyapatite, p. 165. , Takayama Press System Center, JAAS, Tokyo; Ducheyne, P., (1987) J. Biomed. Mater. Res. Appl. Biomater., 21, p. 219; Heughbaert, J.C., Bonel, G., (1986) Biological and Biomechanical Performance of Biomaterials, p. 9. , edited by P. Christel, A. Meunier and A. J. C. Lee Elsevier Science Publishers B.V., Amsterdam; Ellis, L.G., Nelson, D.G.A., Featherstone, J.D.B., (1988) J. Biomed. Mater. Res., 22, p. 541; Raemdonck, W.V., Ducheyne, P., Meester, P.D., (1984) Metal and Ceramic Biomaterials, p. 143. , edited by P. Ducheyne and G. W. Hashi CRC Press, Boca Raton, FL; Shors, E.C., Holmes, R.E., (1993) An Introduction to Bioceramics, p. 181. , edited by L. L. Hench and J. Wilson World Scientific, Hong Kong; Rey, C., (1990) Biomaterials, 11, p. 14; Evans, G., Behiri, J., Currey, J., Bonfield, W., (1990) J. Mater. Sci. Mater. Med., 1, p. 38; Rey, C., Frèche, M., Heughebaert, M., Heughebaert, J.C., Lacout, J.L., Vignoles, M., Bioceramics 4, London, 1991, p. 57. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner (Butterworth-Heinemann, London); With, G., Van Dijk, H., Hattu, N., Prijs, K., (1981) J. Mater. Sci., 16, p. 1592; Akao, M., Aoki, H., Kato, K., (1981) J. Mater. Sci., 16, p. 809; Santos, J., Knowles, J., Reis, R., Monteiro, F., Hastings, G., (1994) Biomaterials, 15, p. 5; Soltesz, U., Richter, H., Kienzler, R., (1987) High Technology Ceramics, p. 110. , Elsevier Science Publishers, B.V., Amsterdam; (1971) Determination Micrographique de la Grosseur du Grain Ferritique ou Austénitique des Aciers; Daculsi, G., LeGeros, R.G., Nery, E., Lynch, K., Kerebel, B., (1989) J. Biomed. Mater. Res., 23, p. 883
Keywords: article; Bending strength; Bone; chemical composition; Composite materials; Composition; Composition effects; glass; Glass composition; Glass reinforced hydroxapatite composite; hydroxyapatite; implant; Magnesium Oxide; metal oxide; Microstructure; molecular dynamics; Phosphates; potassium derivative; priority journal; Sintering; Sintering temperature; sodium derivative; Thermal effects; Trace Elements; Tricalcium phosphate phase; X ray diffraction

Sintering effects in a glass reinforced hydroxyapatite - Knowles, J.C.; Talal, S.; Santos, J.D. (BiomaterialsBIOMATERIALS, 1996)
Glass was incorporated into hydroxyapatite (HA) to act as a sintering aid in order to improve the mechanical properties. The glass was added at 2 and 4 wt% and the powders compacted uniaxially. The compacts were sintered at a variety of temperatures (1200, 1250, 1300 and 1350°C) and the effects of the glass addition and the firing temperature were studied to determine their effects on the sintering process. It was found that the glass promoted some phase changes, related to the amount of glass added to the composite. At 1200 and 1250°C, some β-tricaicium phosphate (TCP) was found with the residual being HA. However, at 1300 and 1350°C, both β- and α-TCP were formed. The 4 wt% addition, as expected, promoted higher levels of secondary phases in the composite. The flexural bend strength (FBS) showed high values and also significant differences dependent on the amount of glass added. A 2 wt% addition gave a gradual increase in FBS with temperature. With a 4 wt% addition there was an increase in FBS, but above 1300°C there was a rapid decrease. These effects were mirrored in the linear shrinkage. Both the linear shrinkage and the FBS results were attributed to both the phase changes occurring and also change in grain size with increasing firing temperature.Glass was incorporated into hydroxyapatite (HA) to act as a sintering aid in order to improve the mechanical properties. The glass was added at 2 and 4 wt% and the powders compacted uniaxially. The compacts were sintered at a variety of temperatures (1200, 1250, 1300 and 1350°C) and the effects of the glass addition and the firing temperature were studied to determine their effects on the sintering process. It was found that the glass promoted some phase changes, related to the amount of glass added to the composite. At 1200 and 1250°C, some β- tricalcium phosphate (TCP) was found with the residual being HA. However, at 1300 and 1350°C, both β- and α-TCP were formed. The 4 wt% addition, as expected, promoted higher levels of secondary phases in the composite. The flexural bend strength (FBS) showed high values and also significant differences dependent on the amount of glass added. A 2 wt% addition gave a gradual increase in FBS with temperature. With a 4 wt% addition there was an increase in FBS, but above 1300°C there was a rapid decrease. These effects were mirrored in the linear shrinkage. Both the linear shrinkage and the FBS results were attributed to both the phase changes occurring and also change in grain size with increasing firing temperature.
Cited By (since 1996): 39Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/0142-9612(96)87287-5PubMed ID: 8830972Language of Original Document: EnglishCorrespondence Address: Knowles, J.C.; Eastman Dental Institute, Queen Mary and Westfield College, Mile End Road, London E1 4NS, United KingdomChemicals/CAS: Durapatite, 1306-06-5References: Currey, J.D., (1984) The Mechanical Adaptations of Bones, , Princeton University Press;Brown, W.E., Chow, L., Chemical composition of bone mineral (1976) Ann Res Mater Sci, 6, pp. 213-226; Glimcher, M.J., Recent studies of the mineral phase in bone and its possible linkage to the organic matrix by protein bound phosphate conds (1984) Phil Trans R Soc Land, B304, pp. 479-508; Cook, S.D., Thomas, K.A., Kay, J.F., Jarcho, M., Hydroxyapatite-coated porous titanium for use as an orthopaedic biologic attachment system (1980) Clin Orthop, 230, pp. 303-312; Patka, P., Den Otter, G., De Groot, K., Driessen, A.A., Reconstruction of large bone defects with calcium phosphate ceramics. An experimental study (1985) Neth J Surg, 37, p. 38; Wolford, L.M., Wardrop, R.W., Hartog, J.M., Coralline porous hydroxyapatite as a bone graft substitute in orthognathic surgery (1987) J Oral Maxillofac Surg, 45, pp. 1034-1042; Santos, J.D., Morrey, S., Hastings, G.W., Monteiro, F.J., The production and characterisation of a hydroxyapatite ceramic material (1991) Bioceramics, Vol 4. Proceedings of the 4th International Symposium on Ceramics in Medicine, 4, pp. 71-78. , Bonfield W, Hastings GW, Tanner KE, eds. London: Butterworth Heinemann; Dörre, E., Dawihl, W., Ceramic hip endoprostheses (1980) Mechanical Properties of Biomaterials, pp. 113-127. , Hastings GW, Williams DF, eds. New York: Wiley; Murray, M.G.S., Ponton, C.B., Marquis, P.M., Emulsion processing of hydroxyapatite (1992) Bioceramics, Vol 4. Proceedings of the 4th International Symposium on Ceramics in Medicine, 4, pp. 15-22. , Kyoto: Kobunshi Kankokai; Puajindanetr, S., Best, S.M., Bonfield, W., Characterisation and sintering of precipitated hydroxyapatite (1994) Br Ceram Trans, 93 (3), pp. 96-99; Knowles, J.C., Bonfield, W., Development of a glass reinforced hydroxyapatite with enhanced mechanical properties. The effect of glass composition on mechanical properties and its relationship to phase changes (1993) J Biomed Mater Res, 27, pp. 159-1598; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., Microstructural characterisation of glass reinforced hydroxyapatite composites (1994) Biomaterials, 15 (1), pp. 5-10; Knowles, J.C., Development of hydroxyapatite with enhanced mechanical properties: Effect of high glass additions on mechanical properties and phase stability of sintered hydroxyapatite (1994) Br Ceram Trans, 93 (3), pp. 100-103; Ruys, A.J., Wei, M., Sorrell, C.C., Dickson, M.R., Brandwood, A., Milthorpe, B.K., Sintering effects on the strength of hydroxyapatite (1995) Biomaterials, 16, pp. 409-415; Santos, J.D., Reis, R.L., Monteiro, F.J., Knowles, J.C., Hastings, G.W., Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions. Structure and properties of the composites (1995) J Mater Sci Mater Med, , to be published; Soltesz, U., Ritcher, H., Keinzler, R., (1987) High Tech Ceramics, p. 110. , Vincenzini P, ed. Amsterdam: Elsevier; Laugier, M.T., New formula for indentation toughness in ceramics (1987) J Mater Sci Lett, 6, pp. 355-356; Knowles, J.C., Abrahams, I., Bonfield, W., Effect of reinforcing glass composition on phase transformation and crystallographic parameters in hydroxyapatite (1993) Bioceramics, 6, pp. 191-196. , Ducheyne P, Christiansen D, eds. Butterworth-Heinemann
Keywords: article; Bending strength; Biomaterials; calcium phosphate; Chemistry, Physical; Durapatite; glass; Glass reinforced hydroxyapatite; Grain growth; hydroxyapatite; priority journal; Sintering; Sintering aid; temperature; tensile strength; Tricalcium phosphate; X-Ray Diffraction

Computerized fetal heart rate analysis in labour based on 2-s sampling. Can it proceed with confidence? [1] - Bernardes, J.; Garrido, A.; Chang, A.; Sahota, D.S.; Reed, N.N.; James, D.K.; Mohajer, M.P. (European Journal of Obstetrics Gynecology and Reproductive BiologyEUR. J. OBSTET. GYNECOL. REPROD. BIOL., 1995)
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: EOGRAdoi: 10.1016/0301-2115(95)02215-SPubMed ID: 8674558Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Instituto Engenharia Biomedica, Praca Coronel Pacheco 1, 4000 Porto, Portugal
Keywords: computer analysis; Computers; Female; Fetal monitoring; fetus; fetus heart rate; Heart Rate, Fetal; human; labor; Labor, Obstetric; letter; measurement; Pregnancy; priority journal; sampling; Time Factors

The effect of hydroxyapatite thickness on metal ion release from stainless steel substrates - Sousa, S.R.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The corrosion behaviour of 350 stainless steel coated with hydroxyapatite, HA, by plasma spraying was studied in Hank's Balanced Salt Solution, HBSS, and compared with that of polished passivated surfaces. Two different nominal thicknesses, 50 μm and 200 μm, corresponding to what one might consider a thin and a thick coating, respectively, were used. Only HA coatings with a thickness of 200 μm were capable of reducing the electrical charge consumed at constant potential to values lower than those measured for polished surfaces. However, no HA detachment occurred for both thicknesses, as opposed to what has been found in a previous work with Ti6A14V alloy coated with 50 μm HA. No iron, chromium or nickel were detected in solution by Atomic Absorption Spectroscopy with electrothermal atomization (ET-AAS). These elements were also absent from the bulk of the HA coating, both after a 6 month immersion period and electrochemical accelerated tests. The data indicate that in spite of the relatively low corrosion resistance of stainless steel as compared to that of titanium alloys, a thin (50 μm) HA coating prevents the release of metal ions, while remaining adherent to the substrate.The corrosion behaviour of 350 stainless steel coated with hydroxyapatite, HA, by plasma spraying was studied in Hank's Balanced Salt Solution, HBSS, and compared with that of polished passivated surfaces. Two different nominal thicknesses, 50 μm and 200 μm, corresponding to what one might consider a thin and a thick coating, respectively, were used. Only HA coatings with a thickness of 200 μm were capable of reducing the electrical charge consumed at constant potential to values lower than those measured for polished surfaces. However, no HA detachment occurred for both thicknesses, as opposed to what has been found in a previous work [1] with Ti6Al4V alloy coated with 50 μm HA. No iron, chromium or nickel were detected in solution by Atomic Absorption Spectroscopy with electrothermal atomization (ET-AAS). These elements were also absent from the bulk of the HA coating, both after a 6 month immersion period and electrochemical accelerated tests. The data indicate that in spite of the relatively low corrosion resistance of stainless steel as compared to that of titanium alloys, a thin (50 μm) HA coating prevents the release of metal ions, while remaining adherent to the substrate.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00134324Language of Original Document: EnglishCorrespondence Address: Sousa, S.R.; INEB, Instituto Engenharia Biomedica, Praca do Coronel Pacheco, 1, 4050 Porto, Portugal
Keywords: Absorption spectroscopy; atomic absorption spectrometry; Atomic absorption spectroscopy; Atomic spectroscopy; balanced salt solution; Calcium Compounds; Chromium; comparative study; conference paper; Corrosion; Corrosion behaviour; Electric charge; electrochemistry; Hank balanced salt solution; hydroxyapatite; immersion; Inorganic coatings; Ions; Iron; metal ion; Metal ion release; Nickel; Plasma spraying; priority journal; Stainless steel; Stainless steel substrates; Substrates; thickness; Thickness effect; Titanium; Titanium alloys

Electrochemical and surface modifications on N +-ion implanted Ti-6A1-4V immersed in HBSS - Leitão, E.; Sa, C.; Silva, R.A.; Barbosa, M.A.; Ali, H. (Corrosion ScienceCorros. Sci., 1995)
The effect of nitrogen-ion implantation on the electrochemical behaviour of Ti-6Al-4V in a simulated physiological solution (HBSS-Hank's balanced salt solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing better the surface prior to biological testing and to choose the most appropriate nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence produced the lowest corrosion rate under passive conditions. The highest fluence originated a large increase in the corrosion rate and inhibited the formation of a calcium- and phosphate-rich layer on the electrode surface. © 1995.
Cited By (since 1996): 37Export Date: 21 November 2012Source: ScopusCODEN: CRRSALanguage of Original Document: EnglishCorrespondence Address: Leitão, E.; INEB-Instituto de Engenharia Biomédica, Praca do Coronel Pacheco, 1, 4050 Porto, Portugal
Keywords: Biological testing; Characterization; Corrosion; Corrosion rate; Cyclic polarization technique; Electrochemical behaviour; electrochemistry; Hank balanced salt solution; Ion implantation; materials testing; Nitrogen ion implanted titanium aluminum vanadium alloy; Nitrogen-ion fluence; Open circuit potential; Passivation; Polarization; Simulated physiological solution; Solutions; Surface modification; Surface treatment; Titanium alloys

In vitro calcification of orthopaedic implant materials - Leitao, E.; Barbosa, M.A.; De Groot, K. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The formation of an apatite-like layer is achieved by immersing Ti6A14V and TiA12.5Fe substrata in Hank's Balanced Salt Solution (HBSS). The layer was characterized by several techniques, namely X-ray microanalysis, X-ray diffraction and X-ray photoelectron spectroscopy. The results suggest that the layer produced by immersion in HBSS is in the form of an amorphous apatite. The pH and the concentrations of calcium and phosphate were monitored as a function of time. In vitro tests with rat bone marrow were performed in order to mimic the bone/biomaterial interface. They were performed on both immersed and non-immersed samples. The in vitro bone marrow results suggest that the apatite-like layer formed may improve the bone bonding characteristics of the studied titanium alloys.The formation of an apatite-like layer is achieved by immersing Ti6Al4V and TiAl2.5Fe substrata in Hank's Balanced Salt Solution (HBSS). The layer was characterized by several techniques, namely X-ray microanalysis, X-ray diffraction and X-ray photoelectron spectroscopy. The results suggest that the layer produced by immersion in HBSS is in the form of an amorphous apatite. The pH and the concentrations of calcium and phosphate were monitored as a function of time. In vitro tests with rat bone marrow were performed in order to mimic the bone/biomaterial interface. They were performed on both immersed and non-immersed samples. The in vitro bone marrow results suggest that the apatite-like layer formed may improve the bone bonding characteristics of the studied titanium alloys.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00134330Language of Original Document: EnglishCorrespondence Address: Leitao, E.; Instituto de Engenharia Biomedica, Faculdade de Engenharia, Universidade do Porto, Praca Coronel Pacheco 1, 4050 Porto, Portugal
Keywords: Amorphous apatite; Amorphous materials; animal cell; Apatite; balanced salt solution; Bone; bone marrow; Calcification; Calcification (biochemistry); Calcium; calcium phosphate; conference paper; Hank balanced salt solution; immersion; implantation; Implants (surgical); metal implantation; Microanalysis; nonhuman; orthopedics; pH; phosphate; Phosphates; priority journal; rat; Spectroscopy; surface property; time; Titanium; Titanium alloys; X ray analysis; X ray diffraction; X ray photoelectron spectroscopy

Liquid phase sintering of hydroxyapatite by phosphate and silicate glass additions: Structure and properties of the composites - Santos, J.D.; Reis, R.L.; Monteiro, F.J.; Knowles, J.C.; Hastings, G.W. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Phosphate- and silicate-based glasses were added to hydroxyapatite in order to improve its mechanical properties and to fabricate composites with different degrees of bioactivity. A strong chemical bonding was obtained between hydroxyapatite and the phosphate-based glasses leading to samples approaching theoretical density, according to density measurements and scanning electron microscopy. Bioglass® additions led to the formation of a complex calcium phosphate silicate which hampered the reinforcement process. The fracture toughness of the hydroxyapatite-glass composites was shown to be within the 1.1-1.2 MPam(1/2) range, which is double that determined for sintered hydroxyapatite. A 2 μm thick apatite layer was observed on the surface of the hydroxyapatite-glass composites after 48 h immersion in a simulated human blood plasma, whereas only a few apatite crystals were detected on sintered hydroxyapatite after 7 days immersion. From the results obtained we anticipate that the composites might show a higher rate of bone bonding, leading to enhanced bioactivity.Phosphate- and silicate-based glasses were added to hydroxyapatite in order to improve its mechanical properties and to fabricate composites with different degrees of bioactivity. A strong chemical bonding was obtained between hydroxyapatite and the phosphate-based glasses leading to samples approaching theoretical density, according to density measurements and scanning electron microscopy. Bioglass (R) additions led to the formation of a complex calcium phosphate silicate which hampered the reinforcement process. The fracture toughness of the hydroxyapatite-glass composites was shown to be within the 1.1-1.2 MPa m 1/2 range, which is double that determined for sintered hydroxyapatite. A 2 μm thick apatite layer was observed on the surface of the hydroxyapatite-glass composites after 48 h immersion in a simulated human blood plasma, whereas only a few apatite crystals were detected on sintered hydroxyapatite after 7 days immersion. From the results obtained we anticipate that the composites might show a higher rate of bone bonding, leading to enhanced bioactivity.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00120303Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-National Inst. Biomedical Engn., Department Metallurgical Engineering, FEUP, University of Porto, Rua dos Bragas 4099-Porto Codex, Portugal
Keywords: Adhesion; article; Bioactivity; Bioglass; Biomaterials; Bone; bone prosthesis; calcium phosphate; chemical binding; Chemical bonds; chemical composition; Chemical structure; Complex calcium phosphate silicate; Composite materials; crystal; density; Density measurement (specific gravity); glass; Human blood plasma; hydroxyapatite; Liquid phase sintering; Mechanical properties; Mechanics; phosphate; Phosphates; plasma; priority journal; Scanning electron microscopy; silicate; Silicates; Sintering; Structure (composition); surface property; thickness

Modifications in the molecular structure of hydroxyapatite induced by titanium ions - Ribeiro, C.C.; Barbosa, M.A.; Machado, A.A.S.C.; Tudor, A.; Davies, M.C. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
The purpose of this study was to contribute to the understanding of the effect of titanium ions released from a metallic substrate on the molecular structure of hydroxyapatite. The effects of pH, time of incubation and concentration of titanium ions were investigated. The solids were analysed by X-ray diffraction, Fourier transform infrared spectroscopy, Fourier transform Raman spectroscopy, energy dispersive X-ray analysis and thermogravimetric analysis. The results clearly indicate the presence of a titanium phosphate, Ti(HPO 4) 2·nH 2O (n = 1-3), which probably has a double layered structure. The formation of this compound is dependent on the titanium concentration and its crystallinity increases with the time of incubation. The purpose of this study was to contribute to the understanding of the effect of titanium ions released from a metallic substrate on the molecular structure of hydroxyapatite. The effects of pH, time of incubation and concentration of titanium ions were investigated. The solids were analysed by X-ray diffraction, Fourier transform infrared spectroscopy, Fourier transform Raman spectroscopy, energy dispersive X-ray analysis and thermogravimetric analysis. The results clearly indicate the presence of a titanium phosphate, Ti(HPO 4) 2·nH 2O (n = 1-3), which probably has a double layered structure. The formation of this compound is dependent on the titanium concentration and its crystallinity increases with the time of incubation.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00134326Language of Original Document: EnglishCorrespondence Address: Ribeiro, C.C.; Instituto de Engenharia Biomedica, Praca do Coronel Pacheco, 1, 4050 Porto, Portugal
Keywords: Calcium Compounds; Chemical structure; Coatings; conference paper; Crystallinity; Crystallization; Dissolution; Energy dispersive x ray analysis; Fourier transform infrared spectroscopy; Fourier transform Raman spectroscopy; hydroxyapatite; Implants (surgical); incubation time; infrared spectroscopy; Ions; metal ion; Molecular Structure; pH; pH effects; phosphate; Phosphates; priority journal; Raman spectrometry; Raman spectroscopy; Thermogravimetric analysis; thermogravimetry; time; Titanium; Titanium compounds; X ray analysis; X ray diffraction

Plasma surface treatment and PACVD on Ti alloys for surgical implants - Rie, K.-T.; Stucky, T.; Silva, R.A.; Leitao, E.; Bordji, K.; Jouzeau, J.-Y.; Mainard, D. (Surface and Coatings TechnologySurf. Coat. Technol., 1995)
To improve the poor surface hardness and wear resistance of titanium alloys used for surgical implants undergoing wear TiA16V4 and TiA15Fe2.5 have been plasma nitrided. TiN and other sublayers are formed by plasma nitriding. To increase the thickness of the outermost TiN layer the samples have been coated with TiN by PACVD following plasma nitriding. The produced layers have been characterized in terms of microstructure, layer composition, hardness depth profiles. The evaluation of corrosion resistance and biocompatibility revealed that the good properties of the untreated alloys have been well preserved. © 1995 Elsevier Science S.A.
Cited By (since 1996): 49Export Date: 21 November 2012Source: Scopusdoi: 10.1016/0257-8972(95)08316-2Language of Original Document: EnglishCorrespondence Address: Rie, K.-T.; Institut für Oberflächentechnik und plasmatechnische Werkstoffentwicklung, Technische Universität Braunschweig, Bienroder Weg 53, D-38108 Braunschweig, Germany
Keywords: Biocompatibility; Biomaterials; Characterization; Chemical vapor deposition; Corrosion resistance; hardness; Implants (surgical); Microstructure; Nitriding; PACVD; Plasma applications; Plasma assisted chemical vapor deposition; Plasma nitriding; Plasma surface treatment; Surface hardness; Surface treatment; Surfaces; Ti alloys; Titanium alloys; Wear resistance

Stainless steel corrosion products cause alterations on mouse spleen cellular populations - Tracana, R.B.; Pereira, M.L.; Abreu, A.M.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systemically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systematically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00121249Language of Original Document: EnglishCorrespondence Address: Tracana, R.B.; Natl. Inst. Biomedical Engineering, INEB, Praca Coronel Pacheco 1, 4000 Porto, Portugal
Keywords: animal cell; animal experiment; animal tissue; Animalia; article; Biocompatibility; biomaterial; cell population; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Corrosion products; Dissolution; electrochemistry; giant cell; histology; immunology; immunotoxicity; Immunotoxicological effects; Ions; Iron; Lymphocyte; lymphocyte subpopulation; male; mouse; Nickel; nonhuman; orthopedic surgery; priority journal; sodium chloride; Spleen; spleen cell; Stainless steel; Steel corrosion; subcutaneous drug administration; toxicity

Surface modifications of glass-reinforced hydroxyapatite composites - Santos, J.D.; Jha, L.J.; Monteiro, F.J. (BiomaterialsBIOMATERIALS, 1995)
Surface modifications of glass-reinforced hydroxyapatite composites immersed in a simulated physiological solution were studied using X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy. In the first stages of the apatite formation process, calcium and silicon ions were leached out from the surface of the composites. After 12 days of immersion, apatite crystals were detected on the surface indicating bioactive behaviour. Sodium ions attributed to sodium sulphate were also found in the apatite layer. Bound water on the surface also increased with immersion time.Surface modifications of glass-reinforced hydroxyapatite composites immersed in a simulated physiological solution were studied using X-ray photoelectron spectroscopy, scanning electron microscopy and energy dispersive X-ray spectroscopy. In the first stages of the apatite formation process, calcium and silicon ions were leached out from the surface of the composites. After 12 days of immersion, apatite crystals were detected on the surface indicating bioactive behaviour. Sodium ions attributed to sodium sulphate were also found in the apatite layer. Bound water on the surface also increased with immersion time.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/0142-9612(95)91124-HPubMed ID: 7492715Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Dept Metallurgical Engineering, FEUP, University of Porto, Rua dos Bragas 4099-Porto Codex, PortugalChemicals/CAS: Biocompatible Materials; Calcium, 7440-70-2; Glass; Hydroxyapatites; Phosphorus, 7723-14-0; Silicon, 7440-21-3; Sodium, 7440-23-5
Keywords: Apatite; article; Bioactive glass; Biocompatible Materials; Biomaterials; Calcium; chemical composition; Composite materials; Electron Probe Microanalysis; glass; Glass reinforced hydroxyapatite composites; Hydrogen-Ion Concentration; hydroxyapatite; Hydroxyapatites; immersion; Ions; Leaching; Microscopy, Electron, Scanning; Phosphates; phosphorus; priority journal; Scanning electron microscopy; Silicon; Sodium; sodium chloride; sodium sulfate; Spectrometry, X-Ray Emission; Spectroscopy; Surface modification; Surface Properties; surface property; Surface treatment; Water; X ray; X ray photoelectron spectroscopy; X ray spectroscopy

Mouse inflammatory response to stainless steel corrosion products - Tracana, R.B.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1994)
Corrosion occurs regularly following long-term implantation of stainless steel. Little is known about the inflammatory and immunological potential of stainless steel corrosion products. AISI 316L stainless steel was anodically dissolved in a physiologically solution, HBSS, through a chronoamperometric process by imposing an external constant current of 0.5 mA. The solution, containing 245 μg of Fe, 112 μg of Cr, 75 μg of Ni and 13 μg of Mo, was injected in the peritoneal cavity of male C57BL/6 mice. Five animals were used per survival period of time: 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were injected with HBSS. For each assay, peritoneal samples were analysed not only for the total number of cells but also for the percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells, which were estimated by differential counting on Wright-stained cytocentrifuge preparations. Our follow-up study showed that stainless steel corrosion products induced an acute inflammatory response for a period of one week as demonstrated by the influx of PMN cells and macrophages. In contrast neither a chronic inflammation nor an immune response was observed indicating that the stainless steel solution caused a minor tissue response.A follow-up study of the changes to mouse peritoneal cell populations, succeeding intraperitoneal injection of stainless steel corrosion products, in order to assess the inflammatory response to such metals was presented. AISI stainless steel was anodically dissolved in a physiologically solution, Hank's balanced salt solution (HBSS), which was injected in the peritoneal cavity of male mice. Five animals were designated per survival time interval of 4, 16, 24, and 48 h, 1, 2, 4, 8 and 16 weeks. Three control mice per survival period of time were treated with HBSS. For each assay, peritoneal samples were tested for total number of cells and percentages of macrophages, lymphocytes and polymorphonuclear (PMN) cells. The follow-up study revealed that stainless steel corrosion products induced an acute inflammatory response for a duration of one week as shown by the influx of PMN cells and macrophages. In contrast, neither a chronic inflammation nor an immune response was noted suggesting that stainless steel solution caused a minor tissue response.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00120337Language of Original Document: EnglishCorrespondence Address: Tracana, R.B.; Nat. Inst. Biomedical Engineering, Praca Coronel Pacheco 14000 Porto, Portugal
Keywords: animal cell; animal experiment; Animalia; article; Assays; Cell Count; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Dissolution; follow up; immune response; immunology; Inflammation; Inflammatory response; Iron; Lymphocyte; Lymphocytes; macrophage; Macrophages; male; metal implantation; Mice (animal); molybdenum; mouse; Nickel; nonhuman; Peritoneal cavity; Polymorphonuclear; polymorphonuclear cell; priority journal; Stainless steel; time; Tissue; Wright stained cytocentrifuge

Stability of hydroxylapatite plasma-sprayed coated Ti-6Al-4V under cyclic bending in simulated physiological solutions - Reis, R.L.; Monteiro, F.J.; Hastings, G.W. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1994)
The aim of this research was to study the stability of plasma-sprayed coated metal systems and to evaluate their susceptibility to the occurrence of corrosion fatigue. Hydroxylapatite plasma-sprayed coated samples of Ti-6Al-4V were studied under cyclic bending. During fatigue testing samples were immersed in a simulated physiological solution and mechanical and electrochemical degradation were monitored. Applied loads were intended to crack the ceramic coating and not the metal substrate. Electrochemical impedance spectroscopy was used to further characterize the electrochemical behaviour. No increase in tendency to corrode was detected in open-circuit corrosion fatigue testing. It appears as if the coating cracking does not increase metal substrate corrosion susceptibility. The coating integrity has been seriously affected, with marked decrease in thickness, due to the synergistic effect of load and presence of simulated body fluids environment. Impedance results, however, show a general tendency to an increase in corrosion kinetics after corrosion fatigue testing.The aim of this research was to study the stability of plasma-sprayed coated metal systems and to evaluate their susceptibility to the occurrence of corrosion fatigue. Hydroxylapatite plasma-sprayed coated samples of Ti-6Al-4V were studied under cyclic bending. During fatigue testing samples were immersed in a simulated physiological solution and mechanical and electrochemical degradation were monitored. Applied loads were intended to crack the ceramic coating and not the metal substrate. Electrochemical impedance spectroscopy was used to further characterize the electrochemical behaviour. No increase in tendency to corrode was detected in open-circuit corrosion fatigue testing. It appears as if the coating cracking does not increase metal substrate corrosion susceptibility. The coating integrity has been seriously affected, with marked decrease in thickness, due to the synergistic effect of load and presence of simulated body fluids environment. Impedance results, however, show a general tendency to an increase in corrosion kinetics after corrosion fatigue testing.
Cited By (since 1996): 35Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00058983Language of Original Document: EnglishCorrespondence Address: Reis, R.L.; INEB-National Inst. Biomedical Engn., Faculty of Engineering, University of Porto, Rua dos Bragas, 4099 Porto Codex, Portugal
Keywords: article; Bending (deformation); biomaterial; biomechanics; body fluid; Ceramic coatings; ceramics; controlled study; Corrosion; Corrosion fatigue; Corrosion susceptibility; Degradation; Electrochemical impedance spectroscopy; electrochemistry; fatigue; Fatigue testing; hydroxyapatite; impedance; mechanical stress; Physiological solutions; Plasma spraying; priority journal; sodium chloride; Solutions; Spectroscopy; Stability; Substrates; thickness; Titanium; Titanium alloys

In vitro immuno-cytotoxicity of iron evaluated by DNA synthesis of human T lymphocytes stimulated via CD2 and CD3 - Carvalho, G.S.; Bravo, I. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1993)
In previous studies it was demonstrated that the in vitro exposure of human lymphocytes to iron, nickel or cobalt salts causes a significant reduction of lymphocytes expressing CD2 and CD3 surface antigens. Since both molecules are involved in T lymphocyte activation, these studies suggest that the above metals might affect T-cell activation and proliferation. Thus a method was developed for the stimulation of lymphocytes in which both CD2 and CD3 molecules were triggered simultaneously. For this purpose an anti-CD3 monoclonal antibody (mAb) was chemically bound to human erythrocytes (HE), forming HEαCD3 conjugates, which were used for lymphocyte stimulation. In this work the effects of iron on lymphocyte proliferation was studied, following stimulation.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00122194Language of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; Natl Inst for Biomedical Engn (INEB), Praca Coronel Pacheco, Porto, Portugal
Keywords: article; Biochemistry; Biomedical engineering; cd2 antigen; cd3 antigen; cd8 antigen; Cell culture; cell stimulation; concentration response; DNA; DNA synthesis; erythrocyte; human; human cell; Human lymphocytes; Immuno-cytotoxicity; immunocytotoxicity; Iron; lymphocyte proliferation; monoclonal antibody; monocyte; Synthesis (chemical); t lymphocyte; toxicity

Stimulation of human T lymphocytes via CD2 and CD3 molecules: establishment of the method and characterisation of proliferating cells. - Bravo, I.; Carvalho, G.S. (CytobiosCytobios, 1993)
The in vitro exposure of human lymphocytes to degradation products (Fe, Ni or Co) of metallic biomaterials causes a significant reduction of lymphocytes expressing the molecules involved in T lymphocyte activation, CD2 and CD3. A method is described which was developed for the stimulation of lymphocytes in which both CD2 and CD3 molecules were triggered simultaneously. For this purpose an anti-CD3 monoclonal antibody (mAb) was chemically bound to sheep (SE) or human (HE) erythrocytes, forming SE alpha CD3 or HE alpha CD3 conjugates, respectively, which were used for lymphocyte stimulation. Stimulation via CD2 and CD3 was compared with classical phytohaemagglutinin stimulation as well as with soluble alpha CD3 mAb stimulation. Phenotypical characterisation of DNA synthesising lymphocytes was assessed by autoradiography of 3H-thymidine pulsed cultures combined with immunocytochemical tests. Results indicate that this method of T lymphocyte stimulation via CD2 and CD3 is reliable and consistent, and it seems to be very convenient for the evaluation of immunocytotoxicity of metal ions derived from metallic biomaterials.
Keywords: Antigens, CD2; Antigens, CD3; Antigens, Differentiation, T Lymphocyte; Antigens, Differentiation, T-Lymphocyte; article; cd2 antigen; cd3 antigen; Cell culture; Cell Division; Cells, Cultured; cytology; human; immunoglobulin receptor; immunology; lymphocyte activation; metabolism; Receptors, Immunologic; t lymphocyte; T lymphocyte antigen; T-Lymphocytes